Ethanol's interaction with BK channel α subunitresidue K361 does not mediate behavioral responses to alcohol in mice. - Okhuarobo A,; Kreifeldt M; Gandhi PJ,; Lopez C; Martinez B; Fleck K; Bajo M,; Bhattacharyya P; Dopico AM; Roberto M; Roberts AJ,; Homanics GE,; et al. (Mol Psychiatry)
Large conductance potassium (BK) channels are among the most sensitive molecular targets of ethanol and genetic variations in the channel-forming α subunit have been nominally associated with alcohol use disorders. However, whether the action of ethanol at BK α influences the motivation to drink alcohol remains to be determined. To address this question, we first tested the effect of systemically administered BK channel modulators on voluntary alcohol consumption in C57BL/6J males. Penitrem A (blocker) exerted dose-dependent effects on moderate alcohol intake, while paxilline (blocker) and BMS-204352 (opener) were ineffective. Because pharmacological manipulations are inherently limited by non-specific effects, we then sought to investigate the behavioral relevance of ethanol’s direct interaction with BK α by introducing in the mouse genome a point mutation known to render BK channels insensitive to ethanol while preserving their physiological function. The BK α K361N substitution prevented ethanol from reducing spike threshold in medial habenula neurons. However, it did not alter acute responses to ethanol in vivo, including ataxia, sedation, hypothermia, analgesia, and conditioned place preference. Furthermore, the mutation did not have reproducible effects on alcohol consumption in limited, continuous, or intermittent access home cage two-bottle choice paradigms conducted in both males and females. Notably, in contrast to previous observations made in mice missing BK channel auxiliary β subunits, the BK α K361N substitution had no significant impact on ethanol intake escalation induced by chronic intermittent alcohol vapor inhalation. It also did not affect the metabolic and locomotor consequences of chronic alcohol exposure. Altogether, these data suggest that the direct interaction of ethanol with BK α does not mediate the alcohol-related phenotypes examined here in mice.

Histone deacetylase inhibitor decreases hyperalgesia in a mouse model of alcohol withdrawal-induced hyperalgesia - Aguilar J; De Carvalho LM; Chen H,; Condon R; Lasek AW,; Pradhan AA (Alcohol, clinical & experimental research)
Background: Alcohol withdrawal-induced hyperalgesia (AWH) is characterized as an increased pain sensitivity observed after cessation of chronic alcohol use. Alcohol withdrawal-induced hyperalgesia can contribute to the negative affective state associated with abstinence and can increase susceptibility to relapse. We aimed to characterize pain sensitivity in mice during withdrawal from two different models of alcohol exposure: chronic drinking in the dark (DID) and the Lieber-DeCarli liquid diet. We also investigated whether treatment with a histone deacetylase (HDAC) inhibitor, suberoylanilide hydroxamic acid (SAHA), could ameliorate AWH in mice treated with the Lieber-DeCarli diet. Methods: Male and female C57BL/6J mice were used for these studies. In the DID model, mice received bottles of 20% ethanol or water during the dark cycle for 4 h per day on four consecutive days per week for 6 weeks. Peripheral mechanical sensitivity was measured weekly the morning of Day 5 using von Frey filaments. In the Lieber-DeCarli model, mice received ethanol (5% v/v) or control liquid diet for 10 days, along with a single binge ethanol gavage (5 g/kg) or control gavage, respectively, on Day 10. Peripheral mechanical sensitivity was measured during the liquid diet administration and at 24 and 72 h into ethanol withdrawal. An independent group of mice that received the Lieber-DeCarli diet were administered SAHA (50 mg/kg, i.p.) during withdrawal. Results: Male mice exhibited mechanical hypersensitivity after consuming ethanol for 5 weeks in the DID procedure. In the Lieber-DeCarli model, ethanol withdrawal led to hyperalgesia in both sexes. Suberoylanilide hydroxamic acid treatment during withdrawal from the ethanol liquid diet alleviated AWH. Conclusions: These results demonstrate AWH in mice after chronic binge drinking in males and after Lieber-DeCarli liquid diet administration in both sexes. Like previous findings in rats, HDAC inhibition reduced AWH in mice, suggesting that epigenetic mechanisms are involved in AWH. Keywords: alcohol withdrawal; allodynia; binge drinking; epigenetic; pain.

It is not just about transcription: involvement of brain RNA splicing in substance use disorders - Carvalho L,; Lasek AW, (ournal of neural transmission (Vienna, Austria : 1996))
Alternative splicing is a co-transcriptional process that significantly contributes to the molecular landscape of the cell. It plays a multifaceted role in shaping gene transcription, protein diversity, and functional adaptability in response to environmental cues. Recent studies demonstrate that drugs of abuse have a profound impact on alternative splicing patterns within different brain regions. Drugs like alcohol and cocaine modify the expression of genes responsible for encoding splicing factors, thereby influencing alternative splicing of crucial genes involved in neurotransmission, neurogenesis, and neuroinflammation. Notable examples of these alterations include alcohol-induced changes in splicing factors such as HSPA6 and PCBP1, as well as cocaine's impact on PTBP1 and SRSF11. Beyond the immediate effects of drug exposure, recent research has shed light on the role of alternative splicing in contributing to the risk of substance use disorders (SUDs). This is exemplified by exon skipping events in key genes like ELOVL7, which can elevate the risk of alcohol use disorder. Lastly, drugs of abuse can induce splicing alterations through epigenetic modifications. For example, cocaine exposure leads to alterations in levels of trimethylated lysine 36 of histone H3, which exhibits a robust association with alternative splicing and serves as a reliable predictor for exon exclusion. In summary, alternative splicing has emerged as a critical player in the complex interplay between drugs of abuse and the brain, offering insights into the molecular underpinnings of SUDs. Keywords: Addiction; Alcohol; Alternative splicing; Cocaine; Spliceosome; Splicing factor; Substance use disorder.

Modeling Brain Gene Expression in Alcohol UseDisorder with Genetic Animal Models - Hitzemann R,; Ozburn AR,; Lockwood D,; Phillips TJ, (Current topics in behavioral neurosciences)
Animal genetic models have and will continue to provide important new information about the behavioral and physiological adaptations associated with alcohol use disorder (AUD). This chapter focuses on two models, ethanol preference and drinking in the dark (DID), their usefulness in interrogating brain gene expression data and the relevance of the data obtained to interpret AUD-related GWAS and TWAS studies. Both the animal and human data point to the importance for AUD of changes in synaptic transmission (particularly glutamate and GABA transmission), of changes in the extracellular matrix (specifically including collagens, cadherins and protocadherins) and of changes in neuroimmune processes. The implementation of new technologies (e.g., cell type-specific gene expression) is expected to further enhance the value of genetic animal models in understanding AUD. Keywords: Alcohol use disorder; Animal genetic models; Brain gene expression; Drinking in the dark; Ethanol preference; GWAS; RNA sequencing; TWAS.

Synaptic Effects Induced by Alcohol. - Lovinger DM; M., Roberto (Current Topics in Behavioral Neurosciences)
Ethanol (EtOH) has effects on numerous cellular molecular targets, and alterations in synaptic function are prominent among these effects. Acute exposure to EtOH activates or inhibits the function of proteins involved in synaptic transmission, while chronic exposure often produces opposing and/or compensatory/homeostatic effects on the expression, localization, and function of these proteins. Interactions between different neurotransmitters (e.g., neuropeptide effects on release of small molecule transmitters) can also influence both acute and chronic EtOH actions. Studies in intact animals indicate that the proteins affected by EtOH also play roles in the neural actions of the drug, including acute intoxication, tolerance, dependence, and the seeking and drinking of EtOH. The present chapter is an update of our previous Lovinger and Roberto (Curr Top Behav Neurosci 13:31–86, 2013) chapter and reviews the literature describing these acute and chronic synaptic effects of EtOH with a focus on adult animals and their relevance for synaptic transmission, plasticity, and behavior.

Cell-type brain-region specific changes in prefrontal cortex of a mouse model of alcohol dependence - Salem NA,; Manzano L; Keist MW; Ponomareva O,; Roberts AJ,; Roberto M; Mayfield RD (Neurobiology of disease, 2024)
he prefrontal cortex is a crucial regulator of alcohol drinking, and dependence, and other behavioral phenotypes associated with AUD. Comprehensive identification of cell-type specific transcriptomic changes in alcohol dependence will improve our understanding of mechanisms underlying the excessive alcohol use associated with alcohol dependence and will refine targets for therapeutic development. We performed single nucleus RNA sequencing (snRNA-seq) and Visium spatial gene expression profiling on the medial prefrontal cortex (mPFC) obtained from C57BL/6 J mice exposed to the two-bottle choice-chronic intermittent ethanol (CIE) vapor exposure (2BC-CIE, defined as dependent group) paradigm which models phenotypes of alcohol dependence including escalation of alcohol drinking. Gene co-expression network analysis and differential expression analysis identified highly dysregulated co-expression networks in multiple cell types. Dysregulated modules and their hub genes suggest novel understudied targets for studying molecular mechanisms contributing to the alcohol dependence state. A subtype of inhibitory neurons was the most alcohol-sensitive cell type and contained a downregulated gene co-expression module; the hub gene for this module is Cpa6, a gene previously identified by GWAS to be associated with excessive alcohol consumption. We identified an astrocytic Gpc5 module significantly upregulated in the alcohol-dependent group. To our knowledge, there are no studies linking Cpa6 and Gpc5 to the alcohol-dependent phenotype. We also identified neuroinflammation related gene expression changes in multiple cell types, specifically enriched in microglia, further implicating neuroinflammation in the escalation of alcohol drinking. Here, we present a comprehensive atlas of cell-type specific alcohol dependence mediated gene expression changes in the mPFC and identify novel cell type-specific targets implicated in alcohol dependence. Keywords: Alcohol dependence; Alcohol dependence cell-type specific responses; Chronic intermittent ethanol exposure; Gene co-expression networks; Multimodal data integration; Single nucleus RNA sequencing; Spatial transcriptomics.

Estrogen signaling in the dorsal raphe regulatesbinge-like drinking in mice - Torres Irizarry VC; Feng B; Yang X; Patel N; Schaul S; Ibrahimi L; Ye H; Luo P; Carrillo-Sáenz L; Lai P; Kota M; Dixit D; et al. (Transl Psychiatry, 2024)
Estrogens promote binge alcohol drinking and contribute to sex differences in alcohol use disorder. However, the mechanisms are largely unknown. This study aims to test if estrogens act on 5-hydroxytryptamine neurons in the dorsal raphe nucleus (5-HTDRN) to promote binge drinking. We found that female mice drank more alcohol than male mice in chronic drinking in the dark (DID) tests. This sex difference was associated with distinct alterations in mRNA expression of estrogen receptor α (ERα) and 5-HT-related genes in the DRN, suggesting a potential role of estrogen/ERs/5-HT signaling. In supporting this view, 5-HTDRN neurons from naïve male mice had lower baseline firing activity but higher sensitivity to alcohol-induced excitation compared to 5-HTDRN neurons from naïve female mice. Notably, this higher sensitivity was blunted by 17β-estradiol treatment in males, indicating an estrogen-dependent mechanism. We further showed that both ERα and ERβ are expressed in 5-HTDRNneurons, whereas ERα agonist depolarizes and ERβ agonist hyperpolarizes 5-HTDRN neurons. Notably, both treatments blocked the stimulatory effects of alcohol on 5-HTDRN neurons in males, even though they have antagonistic effects on the activity dynamics. These results suggest that ERs’ inhibitory effects on ethanol-induced burst firing of 5-HTDRN neurons may contribute to higher levels of binge drinking in females. Consistently, chemogenetic activation of ERα- or ERβ-expressing neurons in the DRN reduced binge alcohol drinking. These results support a model in which estrogens act on ERα/β to prevent alcohol-induced activation of 5-HTDRN neurons, which in return leads to higher binge alcohol drinking.

Mutation of novel ethanol-responsive lncRNA Gm41261 impacts ethanol-relatedbehavioral responses in mice - Plasil SL,; Farris SP,; Blednov Y,; Mayfield RD; Mangieri RA; Nwokeji UJ; Aziz HC,; Lambeth PS; Harris RA; Homanics GE, (Genes, brain, and behavior, 2024)
Chronic alcohol exposure results in widespread dysregulation of gene expression that contributes to the pathogenesis of Alcohol Use Disorder (AUD). Long noncoding RNAs are key regulators of the transcriptome that we hypothesize coordinate alcohol-induced transcriptome dysregulation and contribute to AUD. Based on RNA-Sequencing data of human prefrontal cortex, basolateral amygdala and nucleus accumbens of AUD versus non-AUD brain, the human LINC01265 and its predicted murine homolog Gm41261 (i.e., TX2) were selected for functional interrogation. We tested the hypothesis that TX2 contributes to ethanol drinking and behavioral responses to ethanol. CRISPR/Cas9 mutagenesis was used to create a TX2 mutant mouse line in which 306 base-pairs were deleted from the locus. RNA analysis revealed that an abnormal TX2 transcript was produced at an unchanged level in mutant animals. Behaviorally, mutant mice had reduced ethanol, gaboxadol and zolpidem-induced loss of the righting response and reduced tolerance to ethanol in both sexes. In addition, a male-specific reduction in two-bottle choice every-other-day ethanol drinking was observed. Male TX2 mutants exhibited evidence of enhanced GABA release and altered GABAA receptor subunit composition in neurons of the nucleus accumbens shell. In C57BL6/J mice, TX2 within the cortex was cytoplasmic and largely present in Rbfox3+ neurons and IBA1+ microglia, but not in Olig2+ oligodendrocytes or in the majority of GFAP+ astrocytes. These data support the hypothesis that TX2 mutagenesis and dysregulation impacts ethanol drinking behavior and ethanol-induced behavioral responses in mice, likely through alterations in the GABAergic system. Keywords: CRISPR/Cas9; alcohol use disorder; behavioral analysis; electrophysiology; gene-targeted; genetics; long noncoding RNA; molecular analysis; mouse; mutagenesis.

A reverse translational study of PPAR-α agonist efficacy inhuman and rodent models relevant to alcohol use disorder. - Mason BJ,; Estey D; Roberts A; de Guglielmo G; George O; Light J; Stoolmiller M; Quello S,; Skinner M; Shadan F,; Begovic A; Kyle MC; et al. (Neurobiology of stress, 2024)
Alcohol Use Disorder (AUD) is a chronic relapsing disorder affecting an estimated 283 million individuals worldwide, with substantial health and economic consequences. Peroxisome proliferator-activated receptors (PPARs), particularly PPAR-α and PPAR-γ, have shown promise in preclinical studies as potential therapeutic targets for AUD. In this human laboratory study, we aimed to translate preclinical findings on the PPAR-α agonist fenofibrate to a human population with current AUD. We hypothesized that, relative to placebo, fenofibrate at the highest FDA-approved dose of 145 mg/d would attenuate responsiveness to in vivo alcohol cues in the lab and reduce drinking under natural conditions. However, the results did not show significant differences in craving and alcohol consumption between the fenofibrate and placebo groups. Reverse translational studies in rodent models confirmed the lack of fenofibrate effect at human-equivalent doses. These findings suggest that inadequate translation of drug dose from rodents to humans may account for the lack of fenofibrate effects on alcohol craving and consumption in humans with AUD. The results highlight the need for new brain-penetrant PPAR-α agonists to adequately test the therapeutic potential of PPAR-α agonists for AUD, and the importance of reverse translational approaches and selection of human-equivalent doses in drug development. Keywords: Alcohol use disorder; Fenofibrate; Human laboratory study; Mouse; Peroxisome proliferator-activated receptor-alpha; Rat.

Repurposing anti-inflammatory medications for alcohol and substance use disorders - Ozburn AR,; Spencer SM. (Neuropsychopharmacology : official publication of the American College of Neuropsychopharmacology, 2024)

Pre-clinical and clinical evidence forsuppression of alcohol intake by apremilast. - Grigsby KB,; Mangieri RA; Roberts AJ,; Lopez MF,; Firsick EJ,; Townsley KG,; Beneze A,; Bess J,; Eisenstein TK,; Meissler JJ,; Light JM,; Miller J,; et al. (The Journal of clinical investigation, 2023)
Treatment options for Alcohol Use Disorders (AUD) have minimally advanced since 2004, while the annual deaths and economic toll have increased alarmingly. Phosphodiesterase type 4 (PDE4) is associated with alcohol and nicotine dependence. PDE4 inhibitors were identified as a potential AUD treatment using a novel bioinformatics approach. We prioritized a newer PDE4 inhibitor, apremilast, as ideal for repurposing, (i.e. FDA approved for psoriasis, low incidence of adverse events, excellent safety profile), and tested it using multiple animal strains and models, as well as in a human Phase IIa study. We found that apremilast reduced binge-like alcohol intake and behavioral measures of alcohol motivation in mouse models of genetic risk for drinking to intoxication. Apremilast also reduced excessive alcohol drinking in models for stress-facilitated drinking and alcohol dependence. Using site-directed drug infusions and electrophysiology, we uncovered that apremilast may act to lessen drinking in mice by increasing neural activity in the nucleus accumbens, a key brain region in the regulation of alcohol intake. Importantly, apremilast (90 mg/d) reduced excessive drinking in non-treatment seeking individuals with AUD in a double blind, placebo-controlled study. These results demonstrate that apremilast suppresses excessive alcohol drinking across the spectrum of AUD severity.

Chronic ethanol altersadrenergic receptor gene expression and produces cognitive deficits in male mice. - Athanason AC,; Nadav T,; Cates-Gatto C,; Roberts AJ,; Roberto M; Varodayan FP. (Neurobiology of stress, 2023)
Hyperkateifia and stress-induced alcohol cravings drive relapse in individuals with alcohol use disorder (AUD). The brain stress signal norepinephrine (also known as noradrenaline) tightly controls cognitive and affective behavior and was thought to be broadly dysregulated with AUD. The locus coeruleus (LC) is a major source of forebrain norepinephrine, and it was recently discovered that the LC sends distinct projections to addiction-associated regions suggesting that alcohol-induced noradrenergic changes may be more brain region-specific than originally thought. Here we investigated whether ethanol dependence alters adrenergic receptor gene expression in the medial prefrontal cortex (mPFC) and central amgydala (CeA), as these regions mediate the cognitive impairment and negative affective state of ethanol withdrawal. We exposed male C57BL/6J mice to the chronic intermittent ethanol vapor-2 bottle choice paradigm (CIE-2BC) to induce ethanol dependence, and assessed reference memory, anxiety-like behavior and adrenergic receptor transcript levels during 3-6 days of withdrawal. Dependence bidirectionally altered mouse brain α1 and β receptor mRNA levels, potentially leading to reduced mPFC adrenergic signaling and enhanced noradrenergic influence over the CeA. These brain region-specific gene expression changes were accompanied by long-term retention deficits and a shift in search strategy in a modified Barnes maze task, as well as greater spontaneous digging behavior and hyponeophagia. Current clinical studies are evaluating adrenergic compounds as a treatment for AUD-associated hyperkatefia, and our findings can contribute to the refinement of these therapies by increasing understanding of the specific neural systems and symptoms that may be targeted.

Chronic ethanol induces a pro-inflammatory switch ininterleukin-1β regulation of GABAergic signaling in the medial prefrontal cortex of male mice. - Varodayan FP; Pahng AR,; Davis TD,; Gandhi P,; Bajo M,; Steinman MQ,; Kiosses WB,; Blednov YA,; Burkart MD,; Edwards S,; Roberts AJ,; M., Roberto (Brain, behavior, and immunity, 2023)
Neuroimmune pathways regulate brain function to influence complex behavior and play a role in several neuropsychiatric diseases, including alcohol use disorder (AUD). In particular, the interleukin-1 (IL-1) system has emerged as a key regulator of the brain's response to ethanol (alcohol). Here we investigated the mechanisms underlying ethanol-induced neuroadaptation of IL-1β signaling at GABAergic synapses in the prelimbic region of the medial prefrontal cortex (mPFC), an area responsible for integrating contextual information to mediate conflicting motivational drives. We exposed C57BL/6J male mice to the chronic intermittent ethanol vapor-2 bottle choice paradigm (CIE-2BC) to induce ethanol dependence, and conducted ex vivo electrophysiology and molecular analyses. We found that the IL-1 system regulates basal mPFC function through its actions at inhibitory synapses on prelimbic layer 2/3 pyramidal neurons. IL-1β can selectively recruit either neuroprotective (PI3K/Akt) or pro-inflammatory (MyD88/p38 MAPK) mechanisms to produce opposing synaptic effects. In ethanol naïve conditions, there was a strong PI3K/Akt bias leading to a disinhibition of pyramidal neurons. Ethanol dependence produced opposite IL-1 effects - enhanced local inhibition via a switch in IL-1β signaling to the canonical pro-inflammatory MyD88 pathway. Ethanol dependence also increased cellular IL-1β in the mPFC, while decreasing expression of downstream effectors (Akt, p38 MAPK). Thus, IL-1β may represent a key neural substrate in ethanol-induced cortical dysfunction. As the IL-1 receptor antagonist (kineret) is already FDA-approved for other diseases, this work underscores the high therapeutic potential of IL-1 signaling/neuroimmune-based treatments for AUD.

Editorial: Molecular aspects of compulsive drug use - Lasek AW,; da Silva D,; Choi DS. (Frontiers in psychiatry, 2023)
Drug addiction is a complex psychiatric disorder defined by a compulsion to seek and take the drug, losing control over intake, and continuing to take the drug despite negative consequences. The inability to limit drug consumption leads to relapse and failure in treatment, thus understanding the underlying molecular mechanisms that contribute to compulsive drug seeking and taking is critical to developing effective treatments. The medical term for drug addiction is substance use disorder (SUD), which is defined by an individual having two or more of the 11 criteria that are outlined in the 5th edition of the American Psychiatric Association (1) Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Several criteria for SUD encompass a wide range of indicators that associate with compulsive drug use. These criteria specifically focus on two key aspects: risky use and social impairment. Risky use is characterized by recurrent substance use in physically unsafe environments and persistent substance use despite awareness of potential physical or psychological harm. Social impairment criteria encompass the inability to fulfill major obligations at work, school, or home; continued use of the substance despite significant social or interpersonal problems; and reduction or discontinuation of recreational, social, or occupational activities due to substance use. Despite significant research efforts, the precise molecular mechanisms underlying compulsive drug use in remain largely unknown. However, gaining a deeper understanding of the neurobiological mechanisms that underly compulsive drug taking could lead to novel pharmacological and psychological tools to treat SUD. The papers in this Research Topic, “Molecular aspects of compulsive drug use” provide new knowledge toward achieving this goal. This collection contains preclinical and clinical studies on three different substances: alcohol, cocaine, and methamphetamine. Three of the papers on this topic also have a secondary emphasis on sex differences in compulsive drug use. Women have historically been underrepresented in behavioral neuroscience research but like men, also suffer from SUD. Understanding differences in neurobiology that contribute to sex differences in compulsive drug use will aid in developing effective treatments for both sexes.

Ethanol-induced transcriptional and translational changes in Aldh1l1-Egfp/Rpl10a cortical astrocyte cultures - Hashimoto JG,; Zhang X,; Guizzetti M. (Frontiers in neuroscience, 2023)
The role astrocytes play in brain development and function has garnered greater attention as the diversity of roles they are involved in has become apparent. We have previously shown that ethanol-exposed astrocytes alter neuronal neurite outgrowth in an in vitro co-culture system and that ethanol alters the astrocyte-produced extracellular matrix (ECM) in vitro, with similar alterations in vivo. In this study, we utilized the translating ribosome affinity purification (TRAP) procedure in Aldh1l1-EGFP/Rpl10a transgenic mouse primary cortical astrocyte cultures to transcriptionally and translationally profile the astrocyte response to ethanol. We found a large number of differences between the total RNA pool and the translating RNA pool, indicating that the transcriptional state of astrocytes may not always reflect the translational state of astrocytes. In addition, there was a considerable overlap between ethanol-dysregulated genes in the total RNA pool and the translating RNA pool. Comparisons to published datasets indicate the in vitro model used here is most similar to PD1 or PD7 in vivo cortical astrocytes, and the ethanol-regulated genes showed a significant overlap with models of chronic ethanol exposure in astrocytes, a model of third-trimester ethanol exposure in the hippocampus and cerebellum, and an acute model of ethanol exposure in the hippocampus. These findings will further our understanding of the effects of ethanol on astrocyte gene expression and protein translation and how these changes may alter brain development and support the use of in vitro astrocyte cultures as models of neonatal astrocytes.

IL-18 Signaling in the Rat Central Amygdala Is Disrupted in a Comorbid Model of Post-Traumatic Stress and Alcohol Use Disorder - Borgonetti V,; Cruz B,; Vozella V,; Khom S,; Steinman MQ,; Bullard R,; D'Ambrosio S,; Oleata CS,; Vlkolinsky R,; Bajo M,; Zorrilla EP,; Kirson D,; et al. (Cells, 2023)
Alcohol use disorder (AUD) and anxiety disorders are frequently comorbid and share dysregulated neuroimmune-related pathways. Here, we used our established rat model of comorbid post-traumatic stress disorder (PTSD)/AUD to characterize the interleukin 18 (IL-18) system in the central amygdala (CeA). Male and female rats underwent novel (NOV) and familiar (FAM) shock stress, or no stress (unstressed controls; CTL) followed by voluntary alcohol drinking and PTSD-related behaviors, then all received renewed alcohol access prior to the experiments. In situ hybridization revealed that the number of CeA positive cells for Il18 mRNA increased, while for Il18bp decreased in both male and female FAM stressed rats versus CTL. No changes were observed in Il18r1 expression across groups. Ex vivo electrophysiology showed that IL-18 reduced GABAA-mediated miniature inhibitory postsynaptic currents (mIPSCs) frequencies in CTL, suggesting reduced CeA GABA release, regardless of sex. Notably, this presynaptic effect of IL-18 was lost in both NOV and FAM males, while it persisted in NOV and FAM females. IL-18 decreased mIPSC amplitude in CTL female rats, suggesting postsynaptic effects. Overall, our results suggest that stress in rats with alcohol access impacts CeA IL-18-system expression and, in sex-related fashion, IL-18′s modulatory function at GABA synapses. Keywords: IL-18; post-traumatic stress disorder; alcohol use disorder; CeA; sex differences; GABA

Impact of elevatedbrain IL-6 in transgenic mice on the behavioral and neurochemical consequences ofchronic alcohol exposure. - Gruol DL; Calderon D,; Huitron-Resendiz S,; Cates-Gatto C,; Roberts AJ. (Cells, 2023)
Alcohol consumption activates the neuroimmune system of the brain, a system in which brain astrocytes and microglia play dominant roles. These glial cells normally produce low levels of neuroimmune factors, which are important signaling factors and regulators of brain function. Alcohol activation of the neuroimmune system is known to dysregulate the production of neuroimmune factors, such as the cytokine IL-6, thereby changing the neuroimmune status of the brain, which could impact the actions of alcohol. The consequences of neuroimmune–alcohol interactions are not fully known. In the current studies we investigated this issue in transgenic (TG) mice with altered neuroimmune status relative to IL-6. The TG mice express elevated levels of astrocyte-produced IL-6, a condition known to occur with alcohol exposure. Standard behavioral tests of alcohol drinking and negative affect/emotionality were carried out in homozygous and heterozygous TG mice and control mice to assess the impact of neuroimmune status on the actions of chronic intermittent alcohol (ethanol) (CIE) exposure on these behaviors. The expressions of signal transduction and synaptic proteins were also assessed by Western blot to identify the impact of alcohol–neuroimmune interactions on brain neurochemistry. The results from these studies show that neuroimmune status with respect to IL-6 significantly impacts the effects of alcohol on multiple levels. Keywords: neuroimmune; synaptic transmission; alcohol drinking; depressive-like behavior; STAT3; p42/44MAPK; GABAAR subunits

Inter- and transgenerationalheritability of preconception chronic stress or alcohol exposure: Translational outcomes in brain andbehavior. - Rice RC; Gil DV; Baratta AM,; Frawley RR; Hill SY; Farris SP,; Homanics GE, (Neurobiology of stress, 2023)
Chronic stress and alcohol (ethanol) use are highly interrelated and can change an individual's behavior through molecular adaptations that do not change the DNA sequence, but instead change gene expression. A recent wealth of research has found that these nongenomic changes can be transmitted across generations, which could partially account for the "missing heritability" observed in genome-wide association studies of alcohol use disorder and other stress-related neuropsychiatric disorders. In this review, we summarize the molecular and behavioral outcomes of nongenomic inheritance of chronic stress and ethanol exposure and the germline mechanisms that could give rise to this heritability. In doing so, we outline the need for further research to: (1) Investigate individual germline mechanisms of paternal, maternal, and biparental nongenomic chronic stress- and ethanol-related inheritance; (2) Synthesize and dissect cross-generational chronic stress and ethanol exposure; (3) Determine cross-generational molecular outcomes of preconception ethanol exposure that contribute to alcohol-related disease risk, using cancer as an example. A detailed understanding of the cross-generational nongenomic effects of stress and/or ethanol will yield novel insight into the impact of ancestral perturbations on disease risk across generations and uncover actionable targets to improve human health. Keywords: Alcohol; Epigenetics; Inheritance; Intergenerational; Stress; Transgenerational.

Lysine Methyltransferase SMYD1 Regulates Myogenesis via skNAC Methylation. - Zhu L,; Brown MA,; Sims RJ,; Tiwari GR,; Nie H,; Mayfield RD; Tucker HO. (Cells, 2023)
The SMYD family is a unique class of lysine methyltransferases (KMTases) whose catalytic SET domain is split by a MYND domain. Among these, Smyd1 was identified as a heart- and skeletal muscle-specific KMTase and is essential for cardiogenesis and skeletal muscle development. SMYD1 has been characterized as a histone methyltransferase (HMTase). Here we demonstrated that SMYD1 methylates is the Skeletal muscle-specific splice variant of the Nascent polypeptide-Associated Complex (skNAC) transcription factor. SMYD1-mediated methylation of skNAC targets K1975 within the carboxy-terminus region of skNAC. Catalysis requires physical interaction of SMYD1 and skNAC via the conserved MYND domain of SMYD1 and the PXLXP motif of skNAC. Our data indicated that skNAC methylation is required for the direct transcriptional activation of myoglobin (Mb), a heart- and skeletal muscle-specific hemoprotein that facilitates oxygen transport. Our study revealed that the skNAC, as a methylation target of SMYD1, illuminates the molecular mechanism by which SMYD1 cooperates with skNAC to regulate transcriptional activation of genes crucial for muscle functions and implicates the MYND domain of the SMYD-family KMTases as an adaptor to target substrates for methylation. Keywords: heart and skeletal muscle; methyltransferase; transcriptional regulation.

Negative and positive allosteric modulators of the α7 nicotinic acetylcholine receptor regulates theability of adolescent binge alcohol exposure to enhance adult alcohol consumption. - Rodd ZA; Swartzwelder HS,; Waeiss RA,; Soloviov SO,; Lahiri DK,; Engleman EA,; Truitt WA,; Bell RL,; Hauser SR. (Frontiers in behavioral neuroscience, 2023)
Rationale and Objectives: Ethanol acts directly on the α7 Nicotinic acetylcholine receptor (α7). Adolescent-binge alcohol exposure (ABAE) produces deleterious consequences during adulthood, and data indicate that the α7 receptor regulates these damaging events. Administration of an α7 Negative Allosteric Modulator (NAM) or the cholinesterase inhibitor galantamine can prophylactically prevent adult consequences of ABAE. The goals of the experiments were to determine the effects of co-administration of ethanol and a α7 agonist in the mesolimbic dopamine system and to determine if administration of an α7 NAM or positive allosteric modulator (PAM) modulates the enhancement of adult alcohol drinking produced by ABAE. Methods: In adult rats, ethanol and the α7 agonist AR-R17779 (AR) were microinjected into the posterior ventral tegmental area (VTA), and dopamine levels were measured in the nucleus accumbens shell (AcbSh). In adolescence, rats were treated with the α7 NAM SB-277011-A (SB) or PNU-120596 (PAM) 2 h before administration of EtOH (ABAE). Ethanol consumption (acquisition, maintenance, and relapse) during adulthood was characterized. Results: Ethanol and AR co-administered into the posterior VTA stimulated dopamine release in the AcbSh in a synergistic manner. The increase in alcohol consumption during the acquisition and relapse drinking during adulthood following ABAE was prevented by administration of SB, or enhanced by administration of PNU, prior to EtOH exposure during adolescence. Discussion: Ethanol acts on the α7 receptor, and the α7 receptor regulates the critical effects of ethanol in the brain. The data replicate the findings that cholinergic agents (α7 NAMs) can act prophylactically to reduce the alterations in adult alcohol consumption following ABAE.

Neuroimmune pathways as targets to reduce alcohol consumption. - Grantham EK,; Barchiesi R; Salem NA,; Mayfield RD. (Pharmacology, biochemistry, and behavior, 2023)

RNA biomarkers for alcohol use disorder. - Ferguson LB,; Mayfield RD; Messing RO. (Frontiers in molecular neuroscience, 2023)
Alcohol use disorder (AUD) is highly prevalent and one of the leading causes of disability in the US and around the world. There are some molecular biomarkers of heavy alcohol use and liver damage which can suggest AUD, but these are lacking in sensitivity and specificity. AUD treatment involves psychosocial interventions and medications for managing alcohol withdrawal, assisting in abstinence and reduced drinking (naltrexone, acamprosate, disulfiram, and some off-label medications), and treating comorbid psychiatric conditions (e.g., depression and anxiety). It has been suggested that various patient groups within the heterogeneous AUD population would respond more favorably to specific treatment approaches. For example, there is some evidence that so-called reward-drinkers respond better to naltrexone than acamprosate. However, there are currently no objective molecular markers to separate patients into optimal treatment groups or any markers of treatment response. Objective molecular biomarkers could aid in AUD diagnosis and patient stratification, which could personalize treatment and improve outcomes through more targeted interventions. Biomarkers of treatment response could also improve AUD management and treatment development. Systems biology considers complex diseases and emergent behaviors as the outcome of interactions and crosstalk between biomolecular networks. A systems approach that uses transcriptomic (or other -omic data, e.g., methylome, proteome, metabolome) can capture genetic and environmental factors associated with AUD and potentially provide sensitive, specific, and objective biomarkers to guide patient stratification, prognosis of treatment response or relapse, and predict optimal treatments. This Review describes and highlights state-of-the-art research on employing transcriptomic data and artificial intelligence (AI) methods to serve as molecular biomarkers with the goal of improving the clinical management of AUD. Considerations about future directions are also discussed. Keywords: RNA seq; alcohol dependence; alcoholism; biomarker; microarray; transcriptome.

Selective PDE4B and PDE4D inhibitors produce distinct behavioral responses to ethanol and GABAergic drugs in mice - Blednov YA,; Da Costa A,; Mason S,; Mayfield J,; Messing RO. (Neuropharmacology, 2023)
Apremilast is a phosphodiesterase (PDE) type 4 inhibitor that is nonselective at subtypes PDE4A-D. It modulates ethanol and GABAergic responses via protein kinase A (PKA) phosphorylation of specific GABAA receptor subunits and has opposite effects on ethanol-induced ataxia in wild-type and GABAA β3-S408/409A knock-in mice. We hypothesized that these different effects are due to preferential actions at different PDE4 subtypes. To test this hypothesis, we compared effects of selective PDE4 inhibitors on responses to ethanol and GABAergic drugs in male and female C57BL/6J mice. The PDE4B inhibitor A33 accelerated recovery from ataxia induced by ethanol and diazepam but did not alter ataxia induced by propofol. The PDE4D inhibitor D159687 accelerated recovery from diazepam-induced ataxia but prolonged recovery from ethanol- and propofol-induced ataxia. A33 shortened, while D159687 prolonged, the sedative-hypnotic effects of ethanol. Both drugs shortened diazepam's sedative-hypnotic effects. The modulatory effects of A33 and D159687 were completely prevented by the PKA inhibitor H89. Only D159687 prevented development of acute functional tolerance to ethanol-induced ataxia. D159687 transiently reduced two-bottle choice drinking in male and female mice that had consumed ethanol for 3 weeks and transiently reduced two-bottle choice, every-other-day drinking in male mice. A33 did not alter ethanol drinking in either procedure. Neither drug altered binge-like ethanol consumption or blood ethanol clearance. Thus, D159687 produced behavioral effects similar to apremilast, although it produced a more transient and smaller reduction in drinking. These results indicate that PDE4D inhibition contributes to apremilast's ability to reduce ethanol drinking, whereas PDE4B inhibition is not involved.

Sex differences in hippocampal structural plasticity and glycosaminoglycan disaccharide levels after neonatal handling. - Hashimoto JG,; Singer ML,; Goeke CM,; Zhang F; Song Y,; Xia K,; Linhardt RJ,; Guizzetti M. (Experimental neurology, 2023)
In this study we investigated the effects of a neonatal handling protocol that mimics the handling of sham control pups in protocols of neonatal exposure to brain insults on dendritic arborization and glycosaminoglycan (GAG) levels in the developing brain. GAGs are long, unbranched polysaccharides, consisting of repeating disaccharide units that can be modified by sulfation at specific sites and are involved in modulating neuronal plasticity during brain development. In this study, male and female Sprague-Dawley rats underwent neonatal handling daily between post-natal day (PD)4 and PD9, with brains analyzed on PD9. Neuronal morphology and morphometric analysis of the apical and basal dendritic trees of CA1 hippocampal pyramidal neurons were carried out by Golgi-Cox staining followed by neuron tracing and analysis with the software Neurolucida. Chondroitin sulfate (CS)-, Hyaluronic Acid (HA)-, and Heparan Sulfate (HS)-GAG disaccharide levels were quantified in the hippocampus by Liquid Chromatography/Mass Spectrometry analyses. We found sex by neonatal handling interactions on several parameters of CA1 pyramidal neuron morphology and in the levels of HS-GAGs, with females, but not males, showing an increase in both dendritic arborization and HS-GAG levels. We also observed increased expression of glucocorticoid receptor gene Nr3c1 in the hippocampus of both males and females following neonatal handling suggesting that both sexes experienced a similar stress during the handling procedure. This is the first study to show sex differences in two parameters of brain plasticity, CA1 neuron morphology and HS-GAG levels, following handling stress in neonatal rats. Keywords: Dendritic arborization; Glycosaminoglycans (GAGs); Neonatal handling; Sex differences.

Sex-dependent factors of alcohol and neuroimmune mechanisms - Cruz B,; Borgonetti V,; Bajo M,; M., Roberto (Neurobiology of stress, 2023)
Excessive alcohol use disrupts neuroimmune signaling across various cell types, including neurons, microglia, and astrocytes. The present review focuses on recent, albeit limited, evidence of sex differences in biological factors that mediate neuroimmune responses to alcohol and underlying neuroimmune systems that may influence alcohol drinking behaviors. Females are more vulnerable than males to the neurotoxic and negative consequences of chronic alcohol drinking, reflected by elevations of pro-inflammatory cytokines and inflammatory mediators. Differences in cytokine, microglial, astrocytic, genomic, and transcriptomic evidence suggest females are more reactive than males to neuroinflammatory changes after chronic alcohol exposure. The growing body of evidence supports that innate immune factors modulate synaptic transmission, providing a mechanistic framework to examine sex differences across neurocircuitry. Targeting neuroimmune signaling may be a viable strategy for treating AUD, but more research is needed to understand sex-specific differences in alcohol drinking and neuroimmune mechanisms.

Sexually dimorphic role for insular perineuronal netsin aversion-resistant alcohol consumption. - Martins de Carvalho L,; Chen H,; Sutter M,; Lasek AW. (Front Psychiatry, 2023)
Compulsive alcohol drinking is a key symptom of alcohol use disorder (AUD) that is particularly resistant to treatment. An understanding of the biological factors that underly compulsive drinking will allow for the development of new therapeutic targets for AUD. One animal model of compulsive alcohol drinking involves the addition of bitter-tasting quinine to an ethanol solution and measuring the willingness of the animal to consume ethanol despite the aversive taste. Previous studies have demonstrated that this type of aversion-resistant drinking is modulated in the insular cortex of male mice by specialized condensed extracellular matrix known as perineuronal nets (PNNs), which form a lattice-like structure around parvalbumin-expressing neurons in the cortex. Several laboratories have shown that female mice exhibit higher levels of aversion-resistant ethanol intake but the role of PNNs in females in this behavior has not been examined. Here we compared PNNs in the insula of male and female mice and determined if disrupting PNNs in female mice would alter aversion-resistant ethanol intake. PNNs were visualized in the insula by fluorescent labeling with Wisteria floribunda agglutinin (WFA) and disrupted in the insula by microinjecting chondroitinase ABC, an enzyme that digests the chondroitin sulfate glycosaminoglycan component of PNNs. Mice were tested for aversion-resistant ethanol consumption by the addition of sequentially increasing concentrations of quinine to the ethanol in a two-bottle choice drinking in the dark procedure. PNN staining intensity was higher in the insula of female compared to male mice, suggesting that PNNs in females might contribute to elevated aversion-resistant drinking. However, disruption of PNNs had limited effect on aversion-resistant drinking in females. In addition, activation of the insula during aversion-resistant drinking, as measured by c-fos immunohistochemistry, was lower in female mice than in males. Taken together, these results suggest that neural mechanisms underlying aversion-resistant ethanol consumption differ in males and females.

Synaptogenesis by Cholinergic Stimulation of Astrocytes - Roque PJ,; Barria A,; Zhang X,; Hashimoto JG,; Costa LG,; Guizzetti M. (Research square, 2023)
Astrocytes release numerous factors known to contribute to the process of synaptogenesis, yet knowledge about the signals that control their release is limited. We hypothesized that neuron-derived signals stimulate astrocytes, which respond by signaling back to neurons through the modulation of astrocyte-released synaptogenic factors. Here we investigate the effect of cholinergic stimulation of astrocytes on synaptogenesis in co-cultured neurons. Using a culture system where primary rat astrocytes and primary rat neurons are first grown separately allowed us to independently manipulate astrocyte cholinergic signaling. Subsequent co-culture of pre-stimulated astrocytes with naïve neurons enabled us to assess how prior stimulation of astrocyte acetylcholine receptors uniquely modulates neuronal synapse formation. Pre-treatment of astrocytes with the acetylcholine receptor agonist carbachol increased the expression of synaptic proteins, the number of pre- and postsynaptic puncta, and the number of functional synapses in hippocampal neurons after 24 hours in co-culture. Astrocyte secretion of the synaptogenic protein thrombospondin-1 increased after cholinergic stimulation and the inhibition of the target receptor for thrombospondins prevented the observed increase in neuronal synaptic structures. Thus, we identified a novel mechanism of neuron-astrocyte-neuron communication, i.e. , neuronal release of acetylcholine stimulates astrocytes to release synaptogenic proteins leading to increased synaptogenesis in neurons. This study provides new insights into the role of neurotransmitter receptors in developing astrocytes and into our understanding of the modulation of astrocyte-induced synaptogenesis.

Chronic alcohol induced mechanical allodynia by promoting neuroinflammation: A mouse model of alcohol-evoked neuropathic pain - Borgonetti V,; Roberts AJ,; Bajo M,; Galeotti N,; M., Roberto (British journal of pharmacology, 2023)
Background and purpose: Chronic pain is considered a key factor contributing to alcohol use disorder (AUD). The mechanisms responsible for chronic pain associated with chronic alcohol consumption are unknown. We evaluated the development of chronic pain in a mouse model of alcohol dependence and investigate the role of neuroinflammation. Experimental approach: The chronic-intermittent ethanol two-bottle choice CIE-2BC paradigm generates three groups: alcohol-dependent with escalating alcohol intake, nondependent (moderate drinking) and alcohol-naïve control male and female mice. We measured mechanical allodynia during withdrawal and after the last voluntary drinking. Immunoblotting was used to evaluate the protein levels of IBA-1, CSFR, IL-6, p38 and ERK2/1 in spinal cord tissue of dependent and non-dependent animals. Key results: We found significant escalation of drinking in the dependent group in male and female compared with the non-dependent group. The dependent group developed mechanical allodynia during 72 h of withdrawal, which was completely reversed after voluntary drinking. We observed an increased pain hypersensitivity compared with the naïve in 50% of non-dependent group. Increased IBA-1 and CSFR expression was observed in spinal cord tissue of both hypersensitivity-abstinence related and neuropathy-alcohol mice, and increased IL-6 expression and ERK1/2 activation in mice with hypersensitivity-related to abstinence, but not in mice with alcohol-evoked neuropathic pain. Conclusions and implications: The CIE-2BC model induces two distinct pain conditions specific to the type of ethanol exposure: abstinence-related hypersensitivity in dependent mice and alcohol-evoked neuropathic pain in about a half of the non-dependent mice.

Conserved role for PCBP1 in altered RNA splicing in the hippocampus after chronic alcohol exposure - Carvalho L,; Chen H,; Maienschein-Cline M,; Glover EJ; Pandey SC,; Lasek AW. (Molecular psychiatry, 2023)
We previously discovered using transcriptomics that rats undergoing withdrawal after chronic ethanol exposure had increased expression of several genes encoding RNA splicing factors in the hippocampus. Here, we examined RNA splicing in the rat hippocampus during withdrawal from chronic ethanol exposure and in postmortem hippocampus of human subjects diagnosed with alcohol use disorder (AUD). We found that expression of the gene encoding the splicing factor, poly r(C) binding protein 1 (PCBP1), was elevated in the hippocampus of rats during withdrawal after chronic ethanol exposure and AUD subjects. We next analyzed the rat RNA-Seq data for differentially expressed (DE) exon junctions. One gene, Hapln2, had increased usage of a novel 3' splice site in exon 4 during withdrawal. This splice site was conserved in human HAPLN2 and was used more frequently in the hippocampus of AUD compared to control subjects. To establish a functional role for PCBP1 in HAPLN2 splicing, we performed RNA immunoprecipitation (RIP) with a PCBP1 antibody in rat and human hippocampus, which showed enriched PCBP1 association near the HAPLN2 exon 4 3' splice site in the hippocampus of rats during ethanol withdrawal and AUD subjects. Our results indicate a conserved role for the splicing factor PCBP1 in aberrant splicing of HAPLN2 after chronic ethanol exposure. As the HAPLN2 gene encodes an extracellular matrix protein involved in nerve conduction velocity, use of this alternative splice site is predicted to result in loss of protein function that could negatively impact hippocampal function in AUD.

FKBP5 inhibitors modulate alcohol drinking and trauma-related behaviors ina model of comorbid post-traumatic stress and alcohol use disorder. - Cruz B,; Vozella V,; Carper BA,; Xu JC,; Kirson D,; Hirsch S,; Nolen T,; Bradley L,; Fain K,; Crawford M,; Kosten TR,; Zorrilla EP,; et al. (Neuropsychopharmacology., 2023)
Post-traumatic stress disorder (PTSD) leads to enhanced alcohol drinking and development of alcohol use disorder (AUD). Identifying shared neural mechanisms might help discover new therapies for PTSD/AUD. Here, we employed a rat model of comorbid PTSD/AUD to evaluate compounds that inhibit FK506-binding protein 51 (FKBP5), a co-chaperone modulator of glucocorticoid receptors implicated in stress-related disorders. Male and female rats received a familiar avoidance-based shock stress followed by voluntary alcohol drinking. We then assessed trauma-related behaviors through sleep bout cycles, hyperarousal, fear overgeneralization, and irritability. To evaluate the role of stress and alcohol history on the sensitivity to FKBP5 inhibitors, in two separate studies, we administered two FKBP5 inhibitors, benztropine (Study 1) or SAFit2 (Study 2). FKBP5 inhibitors were administered on the last alcohol drinking session and prior to each trauma-related behavioral assessment. We also measured plasma corticosterone to assess the actions of FKBP5 inhibitors after familiar shock stress and alcohol drinking. Benztropine reduced alcohol preference in stressed males and females, while aggressive bouts were reduced in benztropine-treated stressed females. During hyperarousal, benztropine reduced several startle response outcomes across stressed males and females. Corticosterone was reduced in benztropine-treated stressed males. The selective FKBP5 inhibitor, SAFit2, reduced alcohol drinking in stressed males but not females, with no differences in irritability. Importantly, SAFit2 decreased fear overgeneralization in stressed males and females. SAFit2 also reduced corticosterone across stressed males and females. Neither FKBP5 inhibitor changed sleep bout structure. These findings indicate that FKBP5 inhibitors modulate stress-related alcohol drinking and partially modulate trauma-related behaviors. This work supports the hypothesis that targeting FKBP5 may alleviate PTSD/AUD comorbidity.

Neuroimmune interactions with binge alcohol drinking in the cerebellum of IL-6 transgenic mice. - Gruol DL; Calderon D,; French K,; Melkonian C,; Huitron-Resendiz S,; Cates-Gatto C,; Roberts AJ. (Neuropharmacology, 2023)
The neuroimmune system of the brain, which is comprised primarily of astrocytes and microglia, regulates a variety of homeostatic mechanisms that underlie normal brain function. Numerous conditions, including alcohol consumption, can disrupt this regulatory process by altering brain levels of neuroimmune factors. Alcohol and neuroimmune factors, such as proinflammatory cytokines IL-6 and TNF-alpha, act at similar targets in the brain, including excitatory and inhibitory synaptic transmission. Thus, alcohol-induced production of IL-6 and/or TNF-alpha could be important contributing factors to the effects of alcohol on the brain. Recent studies indicate that IL-6 plays a role in alcohol drinking and the effects of alcohol on the brain activity following the cessation of alcohol consumption (post-alcohol period), however information on these topics is limited. Here we used homozygous and heterozygous female and male transgenic mice with increased astrocyte expression of IL-6 to examined further the interactions between alcohol and IL-6 with respect to voluntary alcohol drinking, brain activity during the post-alcohol period, IL-6 signal transduction, and expression of synaptic proteins. Wildtype littermates (WT) served as controls. The transgenic mice model brain neuroimmune status with respect to IL-6 in subjects with a history of persistent alcohol use. Results showed a genotype dependent reduction in voluntary alcohol consumption in the Drinking in the Dark protocol and in frequency-dependent relationships between brain activity in EEG recordings during the post-alcohol period and alcohol consumption. IL-6, TNF-alpha, IL-6 signal transduction partners pSTAT3 and c/EBP beta, and synaptic proteins were shown to play a role in these genotypic effects.

Sexually dimorphic effects of monoacylglycerol lipase inhibitor MJN110 on stress-related behaviour and drinking in Marchigian Sardinian alcohol-preferring rats. - Vozella V,; Cruz B,; Feldman HC,; Bullard R,; Bianchi PC,; Natividad LA,; Cravatt BF,; Zorrilla EP,; Ciccocioppo R,; M., Roberto (British journal of pharmacology, 2023)
Background and purpose: The endocannabinoid (eCB) system plays an important homeostatic role in the regulation of stress circuits and has emerged as a therapeutic target to treat stress disorders and alcohol use disorder (AUD). Extensive research has elucidated a role for the eCB anandamide (AEA), but less is known about 2-arachidonoylglycerol (2-AG) mediated signalling. Experimental approach: We pharmacologically enhanced eCB signalling by inhibiting the 2-AG metabolizing enzyme, monoacylglycerol lipase (MAGL), in male and female Marchigian Sardinian alcohol-preferring (msP) rats, a model of innate alcohol preference and stress hypersensitivity, and in control Wistar rats. We tested the acute effect of the selective MAGL inhibitor MJN110 in alleviating symptoms of alcohol drinking, anxiety, irritability and fear. Key results: A single systemic administration of MJN110 increased 2-AG levels in the central amygdala, prelimbic and infralimbic cortex but did not acutely alter alcohol drinking. MAGL inhibition reduced aggressive behaviours in female msPs, and increased defensive behaviours in male msPs, during the irritability test. Moreover, in the novelty-induced hypophagia test, MJN110 selectively enhanced palatable food consumption in females, mitigating stress-induced food suppression. Lastly, msP rats showed increased conditioned fear behaviour compared with Wistar rats, and MJN110 reduced context-associated conditioned fear responses, but not cue-probed fear expression, in male msPs. Conclusions and implications: Acute inhibition of MAGL attenuated some stress-related responses in msP rats but not voluntary alcohol drinking. Our results provide new insights into the sex dimorphism documented in stress-induced responses. Sex-specific eCB-based approaches should be considered in the clinical development of therapeutics. Keywords: 2-AG; alcohol use disorder; endocannabinoid system; monoacylglycerol lipase; sex differences; stress.

Transcriptome changes in the nucleus of the solitary tract induced by repeated stress, alcohol dependence, or stress-induced drinking in dependent mice. - Grantham EK,; Tiwari GR,; Ponomereva O,; Harris RA; Lopez MF,; Becker HC,; Mayfield RD. (Neuropharmacology, 2023)
Stress increases alcohol consumption in dependent animals and contributes to the development of alcohol use disorder. The nucleus of the solitary tract (NTS) is a critical brainstem region for integrating and relaying central and peripheral signals to regulate stress responses, but it is not known if it plays a role in alcohol dependence- or in stress-induced escalations in alcohol drinking in dependent mice. Here, we used RNA-sequencing and bioinformatics analyses to study molecular adaptations in the NTS of C57BL/6J male mice that underwent an ethanol drinking procedure that uses exposure to chronic intermittent ethanol (CIE) vapor, forced swim stress (FSS), or both conditions (CIE + FSS). Transcriptome profiling was performed at three different times after the last vapor cycle (0-hr, 72-hr, and 168-hr) to identify changes in gene expression associated with different stages of ethanol intoxication and withdrawal. In the CIE and CIE + FSS groups at 0-hr, there was upregulation of genes enriched for cellular response to type I interferon (IFN) and type I IFN- and cytokine-mediated signaling pathways, while the FSS group showed upregulation of neuronal genes. IFN signaling was the top gene network positively correlated with ethanol consumption levels in the CIE and CIE + FSS groups. Results from different analyses (differential gene expression, weighted gene coexpression network analysis, and rank-rank hypergeometric overlap) indicated that activation of type I IFN signaling would be expected to increase ethanol consumption. The CIE and CIE + FSS groups also shared an immune signature in the NTS as has been demonstrated in other brain regions after chronic ethanol exposure. A temporal-based clustering analysis revealed a unique expression pattern in the CIE + FSS group that suggests the interaction of these two stressors produces adaptations in synaptic and glial functions that may drive stress-induced drinking.

Brain gene expressiondifferences related to ethanol preference in the collaborative cross founder strains. - Anderson JQ,; Darakjian P,; Hitzemann R,; Lockwood DR,; Phillips TJ,; Ozburn AR. (Frontiers in behavioral neuroscience, 2022)
The collaborative cross (CC) founder strains include five classical inbred laboratory strains [129S1/SvlmJ (S129), A/J (AJ), C57BL/6J (B6), NOD/ShiLtJ (NOD), and NZO/HILtJ (NZO)] and three wild-derived strains [CAST/EiJ (CAST), PWK/PhJ (PWK), and WSB/EiJ (WSB)]. These strains encompass 89% of the genetic diversity available in Mus musculus and ∼10–20 times more genetic diversity than found in Homo sapiens. For more than 60 years the B6 strain has been widely used as a genetic model for high ethanol preference and consumption. However, another of the CC founder strains, PWK, has been identified as a high ethanol preference/high consumption strain. The current study determined how the transcriptomes of the B6 and PWK strains differed from the 6 low preference CC strains across 3 nodes of the brain addiction circuit. RNA-Seq data were collected from the central nucleus of the amygdala (CeA), the nucleus accumbens core (NAcc) and the prelimbic cortex (PrL). Differential expression (DE) analysis was performed in each of these brain regions for all 28 possible pairwise comparisons of the CC founder strains. Unique genes for each strain were identified by selecting for genes that differed significantly [false discovery rate (FDR) < 0.05] from all other strains in the same direction. B6 was identified as the most distinct classical inbred laboratory strain, having the highest number of total differently expressed genes (DEGs) and DEGs with high log fold change, and unique genes compared to other CC strains. Less than 50 unique DEGs were identified in common between B6 and PWK within all three brain regions, indicating the strains potentially represent two distinct genetic signatures for risk for high ethanol-preference. 338 DEGs were found to be commonly different between B6, PWK and the average expression of the remaining CC strains within all three regions. The commonly different up-expressed genes were significantly enriched (FDR < 0.001) among genes associated with neuroimmune function. These data compliment findings showing that neuroimmune signaling is key to understanding alcohol use disorder (AUD) and support use of these 8 strains and the highly heterogeneous mouse populations derived from them to identify alcohol-related brain mechanisms and treatment targets.

Effects of a novel beta lactam compound, MC-100093, on the expression of glutamate transporters/receptors and ethanol drinking behavior of alcohol preferring rats. - Alhaddad H,; Wong W,; Abou-Gharbia M,; Childers W,; Melenski E,; Bell RL,; Sari Y, (The Journal of pharmacology and experimental therapeutics, 2022)
Chronic ethanol exposure affects the glutamatergic system in several brain reward regions such as the nucleus accumbens (NAc). Our laboratory has shown that chronic exposure to ethanol reduced the expression of glutamate transporter 1 (GLT-1) and cystine/glutamate exchanger transporter (xCT) and, as a result, increased extracellular glutamate concentrations in the NAc of alcohol preferring (P) rats. Moreover, previous study from our laboratory reported that chronic ethanol intake altered the expression of certain metabotropic glutamate receptors in the brain. In addition to central effects, chronic ethanol consumption induced liver injury, which is associated with steatohepatitis. In the present study, we investigated the effects of chronic ethanol consumption in the brain and liver. Male P rats had access to free choice of ethanol and water bottles for five weeks. Chronic ethanol consumption reduced GLT-1 and xCT expression in the NAc shell but not in the NAc core. Furthermore, chronic ethanol consumption increased fat droplet content as well as peroxisome proliferator-activated receptor alpha (PPAR-α) and GLT-1 expression in the liver. Importantly, treatment with the novel beta-lactam compound, MC-100093, reduced ethanol drinking behavior and normalized the levels of GLT-1 and xCT expression in the NAc shell as well as normalized GLT-1 and PPAR-α expression in the liver. In addition, MC100093 attenuated ethanol-induced increases in fat droplet content in the liver. These findings suggest that MC-100093 might be a potential lead compound to attenuate ethanol-induced dysfunction in glutamatergic system and liver injury. Significance Statement This study identified a novel beta-lactam, MC100093, that has upregulatory effects in GLT-1. MC-100093, reduced ethanol drinking behavior and normalized levels of GLT-1 and xCT expression in the NAc shell as well as normalizing GLT-1 and PPAR-α expression in the liver. In addition, MC100093 attenuated ethanol-induced increases in fat droplet content in the liver.

Alcohol dependence and withdrawal increase sensitivity of central amygdalar GABAergic synapses to the glucocorticoid receptor antagonist mifepristone in male rats. - Khom S,; Rodriguez L; Gandhi P,; Kirson D,; Bajo M,; Oleata CS,; Vendruscolo LF,; Mason BJ,; M., Roberto (Neurobiology of disease, 2022)
Aberrant glucocorticoid signaling via glucocorticoid receptors (GR) plays a critical role in alcohol use disorder (AUD). Acute alcohol withdrawal and protracted abstinence in dependent rats are associated with increased GR signaling and changes in GR-mediated transcriptional activity in the rat central nucleus of the amygdala (CeA). The GR antagonist mifepristone decreases alcohol consumption in dependent rats during acute withdrawal and protracted abstinence. Regulation of CeA synaptic activity by GR is currently unknown. Here, we utilized mifepristone and the selective GR antagonist CORT118335 (both at 10 μM) as pharmacological tools to dissect the role of GR on GABA transmission in male, adult Sprague-Dawley rats using slice electrophysiology. We subjected rats to chronic intermittent alcohol vapor exposure for 5-7 weeks to induce alcohol dependence. A subset of dependent rats subsequently underwent protracted alcohol withdrawal for 2 weeks, and air-exposed rats served as controls. Mifepristone reduced the frequency of pharmacologically-isolated spontaneous inhibitory postsynaptic currents (sIPSC) in the CeA (medial subdivision) without affecting postsynaptic measures in all groups, suggesting decreased GABA release with the largest effect in dependent rats. CORT118335 did not significantly alter GABA transmission in naïve, but decreased sIPSC frequency in dependent rats. Similarly, mifepristone decreased amplitudes of evoked inhibitory postsynaptic potentials only in dependent rats and during protracted withdrawal. Collectively, our study provides insight into regulation of CeA GABAergic synapses by GR. Chronic ethanol enhances the efficiency of mifepristone and CORT118335, thus highlighting the potential of drugs targeting GR as a promising pharmacological avenue for the treatment of AUD.

Alcohol Dependence Induces CRF Sensitivity in Female Central Amygdala GABA Synapses - Rodriguez L; Kirson D,; Wolfe SA,; Patel RR,; Varodayan FP; Snyder AE,; Gandhi PJ,; Khom S,; Vlkolinsky R,; Bajo M,; M., Roberto (International journal of molecular sciences, 2022)
Alcohol use disorder (AUD) is a chronically relapsing disease characterized by loss of control in seeking and consuming alcohol (ethanol) driven by the recruitment of brain stress systems. However, AUD differs among the sexes: men are more likely to develop AUD, but women progress from casual to binge drinking and heavy alcohol use more quickly. The central amygdala (CeA) is a hub of stress and anxiety, with corticotropin-releasing factor (CRF)-CRF1 receptor and Gamma-Aminobutyric Acid (GABA)-ergic signaling dysregulation occurring in alcohol-dependent male rodents. However, we recently showed that GABAergic synapses in female rats are less sensitive to the acute effects of ethanol. Here, we used patch-clamp electrophysiology to examine the effects of alcohol dependence on the CRF modulation of rat CeA GABAergic transmission of both sexes. We found that GABAergic synapses of naïve female rats were unresponsive to CRF application compared to males, although alcohol dependence induced a similar CRF responsivity in both sexes. In situ hybridization revealed that females had fewer CeA neurons containing mRNA for the CRF1 receptor (Crhr1) than males, but in dependence, the percentage of Crhr1-expressing neurons in females increased, unlike in males. Overall, our data provide evidence for sexually dimorphic CeA CRF system effects on GABAergic synapses in dependence.

Alcohol Use Disorder and Its Comorbidity With HIV Infection Disrupts Anterior Cingulate Cortex Functional Connectivity - Honnorat, N,; Fama, R,; Müller-Oehring EM; Zahr NM; Pfefferbaum A,; Sullivan EV; Pohl KM. (Biological psychiatry. Cognitive neuroscience and neuroimaging, 2022)
Background: Individuals with alcohol use disorder (AUD) have a heightened risk of contracting HIV infection. The effects of these two diseases and their comorbidity on brain structure have been well described, but their effects on brain function have never been investigated at the scale of whole-brain connectomes. Methods: In contrast with prior studies that restricted analyses to specific brain networks or examined relatively small groups of participants, our analyses are based on whole-brain functional connectomes of 292 participants. Results: Relative to participants without AUD, the functional connectivity between the anterior cingulate cortex and orbitofrontal cortex was lower for participants with AUD. Compared with participants without AUD+HIV comorbidity, the functional connectivity between the anterior cingulate cortex and hippocampus was lower for the AUD+HIV participants. Compromised connectivity between these pairs was significantly correlated with greater total lifetime alcohol consumption; the effects of total lifetime alcohol consumption on executive functioning were significantly mediated by the functional connectivity between the pairs. Conclusions: Taken together, our results suggest that the functional connectivity of the anterior cingulate cortex is disrupted in individuals with AUD alone and AUD with HIV infection comorbidity. Moreover, the affected connections are associated with deficits in executive functioning, including heightened impulsiveness.

The amygdala noradrenergic system is compromised with alcohol use disorder. - Varodayan FP; Patel RR,; Matzeu A,; Wolfe SA,; Curley DE,; Khom S,; Gandhi PJ,; Rodriguez L; Bajo M,; D'Ambrosio S,; Sun H,; Kerr TM,; et al. (Biological Psychiatry, 2022)
Background: Alcohol use disorder (AUD) is a leading preventable cause of death. The central amygdala (CeA) is a hub for stress and AUD, while dysfunction of the noradrenaline stress system is implicated in AUD relapse. Methods: Here, we investigated whether alcohol (ethanol) dependence and protracted withdrawal alter noradrenergic regulation of the amygdala in rodents and humans. Male adult rats were housed under control conditions, subjected to chronic intermittent ethanol vapor exposure to induce dependence, or withdrawn from chronic intermittent ethanol vapor exposure for 2 weeks, and ex vivo electrophysiology, biochemistry (catecholamine quantification by high-performance liquid chromatography), in situ hybridization, and behavioral brain-site specific pharmacology studies were performed. We also used real-time quantitative polymerase chain reaction to assess gene expression of α1B, β1, and β2 adrenergic receptors in human postmortem brain tissue from men diagnosed with AUD and matched control subjects. Results: We found that α1 receptors potentiate CeA GABAergic (gamma-aminobutyric acidergic) transmission and drive moderate alcohol intake in control rats. In dependent rats, β receptors disinhibit a subpopulation of CeA neurons, contributing to their excessive drinking. Withdrawal produces CeA functional recovery with no change in local noradrenaline tissue concentrations, although there are some long-lasting differences in the cellular patterns of adrenergic receptor messenger RNA expression. In addition, postmortem brain analyses reveal increased α1B receptor messenger RNA in the amygdala of humans with AUD. Conclusions: CeA adrenergic receptors are key neural substrates of AUD. Identification of these novel mechanisms that drive alcohol drinking, particularly during the alcohol-dependent state, supports ongoing new medication development for AUD.

Apremilast-induced increases inacute ethanol intoxication and decreases in ethanol drinking in mice involve PKA phosphorylation ofGABA A β3 subunits. - Blednov YA,; Da Costa A,; Mason S,; Mayfield J,; Moss SJ,; Messing RO. (Neuropharmacology, 2022)
We previously showed that apremilast, an FDA-approved PDE4 inhibitor, selectively alters behavioral responses to ethanol and certain GABAergic drugs in a PKA-dependent manner in C57BL6/J mice. Here, we investigated if PKA phosphorylation of β3 GABAA receptor subunits is involved in apremilast regulation of ethanol, propofol, or diazepam responses. Apremilast prolonged rotarod ataxia and loss of the righting reflex by ethanol and propofol in wild-type mice, but not in β3-S408A/S409A knock-in mice. In contrast, apremilast hastened recovery from the ataxic and sedative effects of diazepam in both genotypes. These findings suggest that apremilast modulation of ethanol and propofol behaviors in wild-type mice is mediated by β3 subunit phosphorylation, whereas its actions on diazepam responses involve a different mechanism. The PKA inhibitor H-89 prevented apremilast modulation of ethanol-induced ataxia. Apremilast sensitized wild-type males to ethanol-induced ataxia and decreased acute functional tolerance (AFT) in females but had no effect in β3-S408A/S409A mice of either sex. These results could not be attributed to genotype differences in blood ethanol clearance. There were also no baseline genotype differences in ethanol consumption and preference in two different voluntary drinking procedures. However, the ability of apremilast to reduce ethanol consumption was diminished in β3-S408A/S409A mice. Our results provide strong evidence that PKA-dependent phosphorylation of β3 GABAA receptor subunits is an important mechanism by which apremilast increases acute sensitivity to alcohol, decreases AFT, and decreases ethanol drinking.

Behavioral profiles of adolescent Alcohol-Preferring/Non-Preferring (P/NP)and High/Low Alcohol-Drinking (HAD/LAD) rats are dependent on line but Not sex. - Lundberg S,; Roman E,; Bell RL. (Frontiers in neuroscience, 2022)
Initial contact with alcohol generally occurs during adolescence, and high consumption during this period is associated with increased risk for later alcohol (AUDs) and/or substance use disorders (SUDs). Rodents selectively bred for high or low alcohol consumption are used to identify behavioral characteristics associated with a propensity for high or low voluntary alcohol intake. The multivariate concentric square field™ (MCSF) is a behavioral test developed to study rodents in a semi-naturalistic setting. Testing in the MCSF creates a comprehensive behavioral profile in a single trial. The current aim was to examine the behavioral profiles of adolescent, bidirectionally selectively bred male and female high alcohol-consuming (P and HAD1/2) and low alcohol-consuming (NP and LAD1/2) rat lines, and outbred Wistar rats. Alcohol-naïve rats were tested once in the MCSF at an age between postnatal days 30 and 35. No common behavioral profile was found for either high or low alcohol-consuming rat lines, and the effect of sex was small. The P/NP and HAD2/LAD2 lines showed within pair-dependent differences, while the HAD1/LAD1 lines were highly similar. The P rats displayed high activity and risk-associated behaviors, whereas HAD2 rats displayed low activity, high shelter-seeking behavior, and open area avoidance. The results from P rats parallel clinical findings that denser family history and risk-taking behavior are strong predictors of future AUDs, often with early onset. Contrarily, the HAD2 behavioral profile was similar to individuals experiencing negative emotionality, which also is associated with a vulnerability to develop, often with a later onset, AUDs and/or SUDs.

Blood and brain gene expression signatures ofchronic intermittent ethanol consumption in mice. - Ferguson LB,; Roberts AJ,; Mayfield RD; Messing RO. (PLoS computational biology, 2022)
Alcohol Use Disorder (AUD) is a chronic, relapsing syndrome diagnosed by a heterogeneous set of behavioral signs and symptoms. There are no laboratory tests that provide direct objective evidence for diagnosis. Microarray and RNA-Seq technologies enable genome-wide transcriptome profiling at low costs and provide an opportunity to identify biomarkers to facilitate diagnosis, prognosis, and treatment of patients. However, access to brain tissue in living patients is not possible. Blood contains cellular and extracellular RNAs that provide disease-relevant information for some brain diseases. We hypothesized that blood gene expression profiles can be used to diagnose AUD. We profiled brain (prefrontal cortex, amygdala, and hypothalamus) and blood gene expression levels in C57BL/6J mice using RNA-seq one week after chronic intermittent ethanol (CIE) exposure, a mouse model of alcohol dependence. We found a high degree of preservation (rho range: [0.50, 0.67]) between blood and brain transcript levels. There was small overlap between blood and brain DEGs, and considerable overlap of gene networks perturbed after CIE related to cell-cell signaling (e.g., GABA and glutamate receptor signaling), immune responses (e.g., antigen presentation), and protein processing / mitochondrial functioning (e.g., ubiquitination, oxidative phosphorylation). Blood gene expression data were used to train classifiers (logistic regression, random forest, and partial least squares discriminant analysis), which were highly accurate at predicting alcohol dependence status (maximum AUC: 90.1%). These results suggest that gene expression profiles from peripheral blood samples contain a biological signature of alcohol dependence that can discriminate between CIE and Air subjects.

Central amygdala corticotropin-releasing factor neurons promote hyponeophagia but do not control alcohol drinking in mice - Kreifeldt M; Herman MA,; Sidhu H; Okhuarobo A,; Macedo GC,; Shahryari R,; Gandhi PJ,; Roberto M; Contet C. (Molecular Psychiatry, 2022)
Corticotropin-releasing factor (CRF) signaling in the central nucleus of the amygdala (CeA) plays a critical role in rodent models of excessive alcohol drinking. However, the source of CRF acting in the CeA during alcohol withdrawal remains to be identified. In the present study, we hypothesized that CeA CRF interneurons may represent a behaviorally relevant source of CRF to the CeA increasing motivation for alcohol via negative reinforcement. We first observed that Crh mRNA expression in the anterior part of the mouse CeA correlates positively with alcohol intake in C57BL/6J males with a history of chronic binge drinking followed by abstinence and increases upon exposure to chronic intermittent ethanol (CIE) vapor inhalation. We then found that chemogenetic activation of CeA CRF neurons in Crh-IRES-Cre mouse brain slices increases gamma-aminobutyric acid (GABA) release in the medial CeA, in part via CRF1 receptor activation. While chemogenetic stimulation exacerbated novelty-induced feeding suppression (NSF) in alcohol-naïve mice, thereby mimicking the effect of withdrawal from CIE, it had no effect on voluntary alcohol consumption, following either acute or chronic manipulation. Furthermore, chemogenetic inhibition of CeA CRF neurons did not affect alcohol consumption or NSF in chronic alcohol drinkers exposed to air or CIE. Altogether, these findings indicate that CeA CRF neurons produce local release of GABA and CRF and promote hyponeophagia in naïve mice, but do not drive alcohol intake escalation or negative affect in CIE-withdrawn mice. The latter result contrasts with previous findings in rats and demonstrates species specificity of CRF circuit engagement in alcohol dependence.

Centralnucleus of the amygdala projections onto the nucleus accumbens core regulate binge-like alcoholdrinking in a CRF-dependent manner. - Borrego MB,; Grigsby KB,; Townsley KG,; Chan A,; Firsick EJ,; Tran A,; Savarese A,; Ozburn AR. (Neuropharmacology, 2022)
Rationale: The nucleus accumbens (NAc) is important for regulating a number of behaviors, including alcohol and substance use. We previously found that chemogenetically manipulating neuronal activity in the NAc core regulates binge-like drinking in mice. The central amygdala (CeA) is also an important regulator of alcohol drinking, and projects to the NAc core. We tested whether neuronal projections from the CeA to the NAc core, or neuropeptides released by the CeA in the NAc core, could regulate binge drinking. Methods: For experiment 1, mice were administered AAV2 Cre-GFP into the NAc core and a Cre-inducible DREADD [AAV2 DIO- hM3Dq, -hM4Di, or -mCherry control] into the CeA. We tested the effects of altering CeA to NAc core activity on binge-like ethanol intake (via "Drinking in the Dark", DID). For experiment 2, we bilaterally microinfused corticotropin releasing factor (CRF), neuropeptide Y (NPY), or somatostatin (SST) into the NAc core prior to DID. For experiment 3, we tested whether intra-NAc CRF antagonism prevented reductions in drinking induced by CNO/hM3Dq stimulation of CeA->NAc projections. Results: Chemogenetically increasing activity in neurons projecting from the CeA to NAc core decreased binge-like ethanol drinking (p < 0.01). Intra-NAc core CRF mimicked chemogenetic stimulation of this pathway (p < 0.05). Binge-like drinking was unaffected by the doses of NPY and SST tested. Lastly, we found that intra-NAc CRF antagonism prevented reductions in drinking induced by chemogenetic stimulation of CeA->NAc projections. These findings demonstrate that neurons projecting from the CeA to NAc core that release CRF are capable of regulating binge-like drinking in mice.

Corticosteronelevels and glucocorticoid receptor gene expression in high drinking in the dark mice and theirheterogeneous stock (HS/NPT) founder line. - Savarese AM,; Grigsby KB,; Jensen BE,; Borrego MB,; Finn DA,; Crabbe JC,; Ozburn AR. (Frontiers in behavioral neuroscience, 2022)
The High Drinking in the Dark (HDID-1) line of mice has been selectively bred for achieving high blood alcohol levels (BALs) in the Drinking in the Dark task, a model of binge-like drinking. Recently, we determined that glucocorticoid receptor (GR) antagonism with either mifepristone or CORT113176 (a selective GR antagonist) reduced binge-like ethanol intake in the HDID-1 mice, but not in their founder line, HS/NPT. Here, we examined whether the selection process may have altered glucocorticoid functioning by measuring (1) plasma corticosterone levels and (2) expression of the genes encoding GR (Nr3c1) and two of its chaperone proteins FKBP51 and FKBP52 (Fkbp5 and Fkbp4) in the brains (nucleus accumbens, NAc) of HDID-1 and HS/NPT mice. We observed no genotype differences in baseline circulating corticosterone levels. However, HDID-1 mice exhibited a greater stimulated peak corticosterone response to an IP injection (of either ethanol or saline) relative to their founder line. We further observed reduced basal expression of Fkbp4 and Nr3c1 in the NAc of HDID-1 mice relative to HS/NPT mice. Finally, HDID-1 mice exhibited reduced Fkbp5 expression in the NAc relative to HS/NPT mice following an injection of 2 g/kg ethanol. Together, these data suggest that selective breeding for high BALs may have altered stress signaling in the HDID-1 mice, which may contribute to the observed selective efficacy of GR antagonism in reducing binge-like ethanol intake in HDID-1, but not HS/NPT mice. These data have important implications for the role that stress signaling plays in the genetic risk for binge drinking.

Effect of abrain-penetrant selective estrogen receptor degrader (SERD) on binge drinking in female mice. - Chen H,; Lu Y,; Xiong R,; Rosales CI,; Coles C,; Hamada K,; Asad N,; Thatcher GRJ,; Lasek AW. (Alcoholism, clinical and experimental research, 2022)
Background: Greater circulating levels of the steroid hormone 17β-estradiol (E2) are associated with higher levels of binge drinking in women. In female mice, estrogen receptors in the ventral tegmental area, a dopaminergic region of the brain involved in the motivation to consume ethanol, regulate binge-like ethanol intake. We recently developed a brain-penetrant selective estrogen receptor degrader (SERD), YL3-122, that could be used to test the behavioral role of brain estrogen receptors. We hypothesized that treating female mice with this compound would reduce binge-like ethanol drinking. Methods: Female C57BL/6J mice were treated systemically with YL3-122 and a related SERD with low brain penetrance, XR5-27, and tested for binge-like ethanol consumption in the drinking in the dark (DID) test. Mice were also tested for sucrose and water consumption and blood ethanol clearance after treatment with the SERDs. Finally, the effect of ethanol exposure on Esr1 gene expression was measured in the ventral tegmental area (VTA), prefrontal cortex (PFC), and ventral hippocampus (vHPC) of male and female mice by quantitative real-time PCR after 4 DID sessions. Results: YL3-122 reduced ethanol consumption when mice were in diestrus but not estrus. YL3-122 also decreased sucrose consumption but did not alter water intake or blood ethanol clearance. XR5-27 did not affect any of these measures. Binge-like ethanol drinking resulted in increased Esr1 transcript in the VTA of both sexes, male vHPC, and female PFC. Conclusions: These results indicate that SERD treatment can decrease binge-like ethanol drinking in female mice. Thus, it could be a novel strategy to reduce binge drinking in women, with the caveat that effectiveness may depend on menstrual cycle phase. In addition, Esr1 transcript is increased by binge ethanol exposure in both sexes but in a brain region-specific manner.

The GPR88 agonist RTI-13951-33 reduces alcohol drinking and seeking in mice. - Ben Hamida S,; Carter M,; Darcq E,; Sourty M,; Rahman MT,; Decker AM,; Jin C,; Kieffer BL., (Addiction Biology, 2022)
GPR88 is an orphan G-protein-coupled receptor that is considered a potential target to treat neuropsychiatric disorders, including addiction. Most knowledge about GPR88 function stems from knockout mouse studies, and in vivo pharmacology is still scarce. Here we examine the effects of the novel brain-penetrant agonist RTI-13951-33 on several alcohol-related behaviours in the mouse. In the intermittent-access-two-bottle-choice paradigm, the compound reduced excessive voluntary alcohol drinking, while water drinking was intact. This was observed for C57BL/6 mice, as well as for control but not Gpr88 knockout mice, demonstrating efficacy and specificity of the drug in vivo. In the drinking-in-the-dark paradigm, RTI-13951-33 also reduced binge-like drinking behaviour for control but not Gpr88 knockout mice, confirming the alcohol consumption-reducing effect and in vivo specificity of the drug. When C57BL/6 mice were trained for alcohol self-administration, RTI-13951-33 decreased the number of nose-pokes over a 4-h session and reduced the number of licks and bursts of licks, suggesting reduced motivation to obtain alcohol. Finally, RTI-13951-33 did not induce any place preference or aversion but reduced the expression of conditioned place preference to alcohol, indicative of a reduction of alcohol-reward seeking. Altogether, data show that RTI-13951-33 limits alcohol intake under distinct conditions that require consummatory behaviour, operant response or association with contextual cues. RTI-13951-33 therefore is a promising lead compound to evaluate GPR88 as a therapeutic target for alcohol use disorders. More broadly, RTI-13951-33 represents a unique tool to better understand GPR88 function, disentangle receptor roles in development from those in the adult and perhaps address other neuropsychiatric disorders.

Hippocampal β2-GABA A receptors mediate LTP suppression by etomidate and contribute to long-lasting feedback butnot feedforward inhibition of pyramidal neurons. - Figueroa AG,; Benkwitz C,; Surges G,; Kunz N,; Homanics GE,; Pearce RA. (Journal of neurophysiology, 2022)
The general anesthetic etomidate, which acts through γ-aminobutyric acid type A (GABAA) receptors, impairs the formation of new memories under anesthesia. This study addresses the molecular and cellular mechanisms by which this occurs. Here, using a new line of genetically engineered mice carrying the GABAA receptor (GABAAR) β2-N265M mutation, we tested the roles of receptors that incorporate GABAA receptor β2 versus β3 subunits to suppression of long-term potentiation (LTP), a cellular model of learning and memory. We found that brain slices from β2-N265M mice resisted etomidate suppression of LTP, indicating that the β2-GABAARs are an essential target in this model. As these receptors are most heavily expressed by interneurons in the hippocampus, this finding supports a role for interneuron modulation in etomidate control of synaptic plasticity. Nevertheless, β2 subunits are also expressed by pyramidal neurons, so they might also contribute. Therefore, using a previously established line of β3-N265M mice, we also examined the contributions of β2- versus β3-GABAARs to GABAA,slow dendritic inhibition, because dendritic inhibition is particularly well suited to controlling synaptic plasticity. We also examined their roles in long-lasting suppression of population activity through feedforward and feedback inhibition. We found that both β2- and β3-GABAARs contribute to GABAA,slow inhibition and that both β2- and β3-GABAARs contribute to feedback inhibition, whereas only β3-GABAARs contribute to feedforward inhibition. We conclude that modulation of β2-GABAARs is essential to etomidate suppression of LTP. Furthermore, to the extent that this occurs through GABAARs on pyramidal neurons, it is through modulation of feedback inhibition.NEW & NOTEWORTHY Etomidate exerts its anesthetic actions through GABAA receptors. However, the mechanism remains unknown. Here, using a hippocampal brain slice model, we show that β2-GABAARs are essential to this effect. We also show that these receptors contribute to long-lasting dendritic inhibition in feedback but not feedforward inhibition of pyramidal neurons. These findings hold implications for understanding how anesthetics block memory formation and, more generally, how inhibitory circuits control learning and memory.

Regulation of alcohol drinking by ventral striatum and extendedamygdala circuitry. - Borrego MB,; Chan AE,; Ozburn AR. (Neuropharmacology, 2022)
Alcohol use disorder is a complex psychiatric disorder that can be modeled in rodents using a number of drinking paradigms. Drinking-in-the-dark (DID) is widely used to model the binge/intoxication stage of addiction, and chronic intermittent ethanol vapor procedures (CIE) are used to induce dependence and model withdrawal/negative affect induced escalation of drinking. We discuss experiments showing the ventral striatum (vStr) and extended amygdala (EA) are engaged in response to ethanol in rodents through c-Fos/Fos immunoreactivity studies. We also discuss experiments in rodents that span a wide variety of techniques where the function of vStr and EA structures are changed following DID or CIE, and the role of neurotransmitter and neuropeptide systems studies in these ethanol-related outcomes. We note where signaling systems converge across regions and paradigms and where there are still gaps in the literature. Dynorphin/κ-opioid receptor (KOR) signaling, as well as corticotropin releasing factor (CRF)/CRF receptor signaling were found to be important regulators of drinking behaviors across brain regions and drinking paradigms. Future research will require that females and a variety of rodent strains are used in preclinical experiments in order to strengthen the generalizability of findings and improve the likelihood of success for testing potential therapeutics in human laboratory studies.

Synaptic effects of IL-1β and CRF in the central amygdala after protracted alcohol abstinence in male rhesus macaques - Patel RR,; Varodayan FP; Herman MA,; Jimenez V,; Agnore R,; Gao L,; Bajo M,; Cuzon Carlson VC,; Walter NA,; Fei SS,; Grant KA,; M., Roberto (Neuropsychopharmacology : official publication of the American College of Neuropsychopharmacology, 2022)
A major barrier to remission from an alcohol use disorder (AUD) is the continued risk of relapse during abstinence. Assessing the neuroadaptations after chronic alcohol and repeated abstinence is important to identify mechanisms that may contribute to relapse. In this study, we used a rhesus macaque model of long-term alcohol use and repeated abstinence, providing a platform to extend mechanistic findings from rodents to primates. The central amygdala (CeA) displays elevated GABA release following chronic alcohol in rodents and in abstinent male macaques, highlighting this neuroadaptation as a conserved mechanism that may underlie excessive alcohol consumption. Here, we determined circulating interleukin-1β (IL-1β) levels, CeA transcriptomic changes, and the effects of IL-1β and corticotropin releasing factor (CRF) signaling on CeA GABA transmission in male controls and abstinent drinkers. While no significant differences in peripheral IL-1β or the CeA transcriptome were observed, pathway analysis identified several canonical immune-related pathways. We addressed this potential dysregulation of CeA immune signaling in abstient drinkers with an electrophysiological approach. We found that IL-1β decreased CeA GABA release in controls while abstinent drinkers were less sensitive to IL-1β's effects, suggesting adaptations in the neuromodulatory role of IL-1β. In contrast, CRF enhanced CeA GABA release similarly in controls and abstinent drinkers, consistent with rodent studies. Notably, CeA CRF expression was inversely correlated with intoxication, suggesting that CRF levels during abstinence may predict future intoxication. Together, our findings highlight conserved and divergent actions of chronic alcohol on neuroimmune and stress signaling on CeA GABA transmission across rodents and macaques.

The synaptic interactions of alcohol and the endogenous cannabinoidsystem. - Wolfe SA,; Vozella V,; M., Roberto (Alcohol research:current reviews, 2022)
Purpose: A growing body of evidence has implicated the endocannabinoid (eCB) system in the acute, chronic, and withdrawal effects of alcohol/ethanol on synaptic function. These eCB-mediated synaptic effects may contribute to the development of alcohol use disorder (AUD). Alcohol exposure causes neurobiological alterations similar to those elicited by chronic cannabinoid (CB) exposure. Like alcohol, cannabinoids alter many central processes, such as cognition, locomotion, synaptic transmission, and neurotransmitter release. There is a strong need to elucidate the effects of ethanol on the eCB system in different brain regions to understand the role of eCB signaling in AUD. Search methods: For the scope of this review, preclinical studies were identified through queries of the PubMed database. Search results: This search yielded 459 articles. Clinical studies and papers irrelevant to the topic of this review were excluded. Discussion and conclusions: The endocannabinoid system includes, but is not limited to, cannabinoid receptors 1 (CB1), among the most abundantly expressed neuronal receptors in the brain; cannabinoid receptors 2 (CB2); and endogenously formed CB1 ligands, including arachidonoylethanolamide (AEA; anandamide), and 2-arachidonoylglycerol (2-AG). The development of specific CB1 agonists, such as WIN 55,212-2 (WIN), and antagonists, such as SR 141716A (rimonabant), provide powerful pharmacological tools for eCB research. Alcohol exposure has brain region-specific effects on the eCB system, including altering the synthesis of endocannabinoids (e.g., AEA, 2-AG), the synthesis of their precursors, and the density and coupling efficacy of CB1. These alcohol-induced alterations of the eCB system have subsequent effects on synaptic function including neuronal excitability and postsynaptic conductance. This review will provide a comprehensive evaluation of the current literature on the synaptic interactions of alcohol exposure and eCB signaling systems, with an emphasis on molecular and physiological synaptic effects of alcohol on the eCB system. A limited volume of studies has focused on the underlying interactions of alcohol and the eCB system at the synaptic level in the brain. Thus, the data on synaptic interactions are sparse, and future research addressing these interactions is much needed.

Translational structural and functional signatures of chronic alcohol effects in mice. - Degiorgis L,; Arefin TM,; Ben-Hamida S,; Noblet V,; Antal C,; Bienert T,; Reisert M,; von Elverfeldt D,; Kieffer BL,; Harsan LA. (Biological Psychiatry, 2022)
Background: Alcohol acts as an addictive substance that may lead to alcohol use disorder. In humans, magnetic resonance imaging showed diverse structural and functional brain alterations associated with this complex pathology. Single magnetic resonance imaging modalities are used mostly but are insufficient to portray and understand the broad neuroadaptations to alcohol. Here, we combined structural and functional magnetic resonance imaging and connectome mapping in mice to establish brain-wide fingerprints of alcohol effects with translatable potential. Methods: Mice underwent a chronic intermittent alcohol drinking protocol for 6 weeks before being imaged under medetomidine anesthesia. We performed open-ended multivariate analysis of structural data and functional connectivity mapping on the same subjects. Results: Structural analysis showed alcohol effects for the prefrontal cortex/anterior insula, hippocampus, and somatosensory cortex. Integration with microglia histology revealed distinct alcohol signatures, suggestive of advanced (prefrontal cortex/anterior insula, somatosensory cortex) and early (hippocampus) inflammation. Functional analysis showed major alterations of insula, ventral tegmental area, and retrosplenial cortex connectivity, impacting communication patterns for salience (insula), reward (ventral tegmental area), and default mode (retrosplenial cortex) networks. The insula appeared as a most sensitive brain center across structural and functional analyses. Conclusions: This study demonstrates alcohol effects in mice, which possibly underlie lower top-down control and impaired hedonic balance documented at the behavioral level, and aligns with neuroimaging findings in humans despite the potential limitation induced by medetomidine sedation. This study paves the way to identify further biomarkers and to probe neurobiological mechanisms of alcohol effects using genetic and pharmacological manipulations in mouse models of alcohol drinking and dependence.

Alcohol's effects on the mouse brain aremodulated by age and sex. - Piekarski DJ,; Zahr NM; Zhao Q; Sullivan EV; Pfefferbaum A. (Addiction Biology, 2022)
Binge alcohol consumption is common among adolescents and may impair normal brain development. Emerging, longitudinal studies in adolescents suggest that the effects of binge alcohol exposure on brain structure differ between sexes. To test the hypothesis that the effects of binge alcohol exposure on developmental brain growth trajectories are influenced by age of exposure and sex, adolescent and adult, male and female C57Bl/6 mice (n = 32), were exposed to a binge-like ethanol (EtOH) exposure paradigm (i.e., 5 cycles of 2 on/2 off days of 5 g/kg EtOH intraperitoneal) or served as saline controls. Longitudinal structural magnetic resonance imaging was acquired at baseline, following binge EtOH exposure, and after 2 weeks of recovery. Alcohol treatment showed interactions with age and sex in altering whole brain volume: adolescents of both sexes demonstrated inhibited whole brain growth relative to their control counterparts, although significance was only attained in female mice which showed a larger magnitude response to EtOH compared to male mice. In region of interest analyses, the somatosensory cortex and cerebellum showed inhibited growth in male and female adolescent mice exposed to EtOH, but the difference relative to controls did not reach multiple comparison-corrected statistical significance. These data suggest that in mice exposed to binge EtOH treatment, adolescent age of exposure and female sex may confer a higher risk to the detrimental effects of EtOH on brain structure and reinforce the need for direct testing of both sexes.

Effect of Chronic IntermittentEthanol Vapor Exposure on RNA Content of Brain-Derived Extracellular Vesicles. - Baratta AM,; Mangieri RA; Aziz HC,; Lopez MF,; Farris SP,; Homanics GE. (Alcohol (Fayetteville, N.Y.), 2022)
Extracellular vesicles (EVs) are important players in normal biological function and disease pathogenesis. Of the many biomolecules packaged into EVs, coding and noncoding RNA transcripts are of particular interest for their ability to significantly alter cellular and molecular processes. Here we investigate how chronic ethanol exposure impacts EV RNA cargo and the functional outcomes of these changes. Following chronic intermittent ethanol (CIE) vapor exposure, EVs were isolated from male and female C57BL/6J mouse brain. Total RNA from EVs was analyzed by lncRNA/mRNA microarray to survey changes in RNA cargo following vapor exposure. Differential expression analysis of microarray data revealed a number of lncRNA and mRNA differentially expressed in CIE compared to control EVs. Weighted gene co-expression network analysis identified multiple male and female specific modules related to neuroinflammation, cell death, demyelination, and synapse organization. To functionally test these changes, whole cell voltage clamp recordings was used to assess synaptic transmission. Incubation of nucleus accumbens brain slices with EVs led to a reduction in spontaneous excitatory postsynaptic current amplitude, although no changes in synaptic transmission were observed between control and CIE EV administration. These results indicate that CIE vapor exposure significantly changes the RNA cargo of brain-derived EVs, which have the ability to impact neuronal function.

Ethanol withdrawal-induced adaptationsin prefrontal corticotropin releasing factor receptor 1-expressing neurons regulate anxiety andconditioned rewarding effects of ethanol. - Patel RR,; Wolfe SA,; Borgonetti V,; Gandhi PJ,; Rodriguez L; Snyder AE,; D'Ambrosio S,; Bajo M,; Domissy A,; Head S,; Contet C; Dayne Mayfield R,; et al. (Molecular Psychiatry, 2022)
Prefrontal circuits are thought to underlie aberrant emotion contributing to relapse in abstinence; however, the discrete cell-types and mechanisms remain largely unknown. Corticotropin-releasing factor and its cognate type-1 receptor, a prominent brain stress system, is implicated in anxiety and alcohol use disorder (AUD). Here, we tested the hypothesis that medial prefrontal cortex CRF1-expressing (mPFCCRF1+) neurons comprise a distinct population that exhibits neuroadaptations following withdrawal from chronic ethanol underlying AUD-related behavior. We found that mPFCCRF1+ neurons comprise a glutamatergic population with distinct electrophysiological properties and regulate anxiety and conditioned rewarding effects of ethanol. Notably, mPFCCRF1+neurons undergo unique neuroadaptations compared to neighboring neurons including a remarkable decrease in excitability and glutamatergic signaling selectively in withdrawal, which is driven in part by the basolateral amygdala. To gain mechanistic insight into these electrophysiological adaptations, we sequenced the transcriptome of mPFCCRF1+ neurons and found that withdrawal leads to an increase in colony-stimulating factor 1 (CSF1) in this population. We found that selective overexpression of CSF1 in mPFCCRF1+ neurons is sufficient to decrease glutamate transmission, heighten anxiety, and abolish ethanol reinforcement, providing mechanistic insight into the observed mPFCCRF1+ synaptic adaptations in withdrawal that drive these behavioral phenotypes. Together, these findings highlight mPFCCRF1+ neurons as a critical site of enduring adaptations that may contribute to the persistent vulnerability to ethanol misuse in abstinence, and CSF1 as a novel target for therapeutic intervention for withdrawal-related negative affect.

Long-term alcohol drinking in High Drinking in the Dark mice is stable for many months and does not show alcohol deprivation effects - Crabbe JC,; Hack WR,; Ozburn AR,; Savarese AM,; Metten P, (Addiction Biology, 2022)
We have modelled genetic risk for binge-like drinking by selectively breeding High Drinking in the Dark-1 and -2 (HDID-1 and HDID-2) mice for their propensity to reach intoxicating blood alcohol levels (BALs) after binge-like drinking in a single bottle, limited access paradigm. Interestingly, in standard two-bottle choice (2BC) tests for continuously available alcohol versus water, HDID mice show modest levels of preference. This indicates some degree of independence of the genetic contributions to risk for binge-like and sustained, continuous access drinking. We had few data where the drinking in the dark (DID) tests of binge-like drinking had been repeatedly performed, so we serially offered multiple DID tests to see whether binge-like drinking escalated. It did not. We also asked whether HDID mice would escalate their voluntary intake with prolonged exposure to alcohol 2BC. They did not. Lastly, we assessed whether an alcohol deprivation effect (ADE) developed. ADE is a temporary elevation in drinking typically observed after a period of abstinence from sustained access to alcohol choice. With repetition, these periods of ADE sometimes have led to more sustained elevations in drinking. We therefore asked whether repeated ADE episodes would elevate choice drinking in HDID mice. They did not. After nearly 500 days of alcohol access, the intake of HDID mice remained stable. We conclude that a genetically-enhanced high risk for binge-like drinking is not sufficient to yield alterations in long-term alcohol intake.

Neuroimaging in alcohol use disorder: From mouse to man. - Fritz, M; Klawonn, AM; Zahr, NM (J Neurosci, 2022)
This article provides an overview of recent advances in understanding the effects of alcohol use disorders (AUD) on the brain from the perspective of magnetic resonance imaging (MRI) research in preclinical models and clinical studies. As a noninvasive investigational tool permitting assessment of morphological, metabolic, and hemodynamic changes over time, MRI offers insight into the dynamic course of alcoholism beginning with initial exposure through periods of binge drinking and escalation, sobriety, and relapse and has been useful in differential diagnosis of neurological diseases associated with AUD. Structural MRI has revealed acute and chronic effects of alcohol on both white and gray matter volumes. MR Spectroscopy, able to quantify brain metabolites in vivo, has shed light on biochemical alterations associated with alcoholism. Diffusion tensor imaging permits microstructural characterization of white matter fiber tracts. Functional MRI has allowed for elucidation of hemodynamic responses at rest and during task engagement. Positron emission tomography, a non-MRI imaging tool, has led to a deeper understanding of alcohol-induced receptor and neurotransmitter changes during various stages of drinking and abstinence. Together, such in vivo imaging tools have expanded our understanding of the dynamic course of alcoholism including evidence for regional specificity of the effects of AUD, hints at mechanisms underlying the shift from casual to compulsive use of alcohol, and profound recovery with sustained abstinence.

Sex Differences in the Brain Transcriptome Related to Alcohol Effects and Alcohol Use Disorder - Hitzemann R,; Bergeson SE,; Berman AE,; Bubier JA,; Chesler EJ,; Finn DA,; Hein M,; Hoffman P,; Holmes A,; Kisby BR,; Lockwood D,; Lodowski KH,; et al. (Biol Psychiatry, 2022)
There is compelling evidence that sex and gender have crucial roles in excessive alcohol (ethanol) consumption. Here, we review some of the data from the perspective of brain transcriptional differences between males and females, focusing on rodent animal models. A key emerging transcriptional feature is the role of neuroimmune processes. Microglia are the resident neuroimmune cells in the brain and exhibit substantial functional differences between males and females. Selective breeding for binge ethanol consumption and the impacts of chronic ethanol consumption and withdrawal from chronic ethanol exposure all demonstrate sex-dependent neuroimmune signatures. A focus is on resolving sex-dependent differences in transcriptional responses to ethanol at the neurocircuitry level. Sex-dependent transcriptional differences are found in the extended amygdala and the nucleus accumbens. Telescoping of ethanol consumption is found in some, but not all, studies to be more prevalent in females. Recent transcriptional studies suggest that some sex differences may be due to female-dependent remodeling of the primary cilium. An interesting theme appears to be developing: at least from the animal model perspective, even when males and females are phenotypically similar, they differ significantly at the level of the transcriptome.

Age differences in brain structural and metabolic responses to binge ethanol exposure in fisher 344 rats - Zahr N,; Sullivan E,; Pohl K,; Pfefferbaum A, (Neuropsychopharmacology, 2021)
An overarching goal of our research has been to develop a valid animal model of alcoholism with similar imaging phenotypes as those observed in humans with the ultimate objective of assessing the effectiveness of pharmacological agents. In contrast to our findings in humans with alcohol use disorders (AUD), our animal model experiments have not demonstrated enduring brain pathology despite chronic, high ethanol (EtOH) exposure protocols. Relative to healthy controls, older individuals with AUD demonstrate accelerating brain tissue loss with advanced age. Thus, this longitudinally controlled study was conducted in 4-month old (equivalent to ~16-year-old humans) and 17-month old (equivalent to ~45-year-old humans) male and female Fisher 344 rats to test the hypothesis that following equivalent alcohol exposure protocols, older relative to younger animals would exhibit more brain changes as evaluated using in vivo structural magnetic resonance imaging (MRI) and MR spectroscopy (MRS). At baseline, total brain volume as well as the volumes of each of the three constituent tissue types (i.e., cerebral spinal fluid (CSF), gray matter, white matter) were greater in old relative to young rats. Baseline metabolite levels (except for glutathione) were higher in older than younger animals. Effects of binge EtOH exposure on brain volumes and neurometabolites replicated our previous findings in Wistar rats and included ventricular enlargement and reduced MRS-derived creatine levels. Brain changes in response to binge EtOH treatment were more pronounced in young relative to older animals, negating our hypothesis. Higher baseline glutathione levels in female than male rats suggest that female rats are perhaps protected against the more pronounced changes in CSF and gray matter volumes observed in male rats due to superior metabolic homeostasis mechanisms. Additional metabolite changes including low inositol levels in response to high blood alcohol levels support a mechanism of reversible osmolarity disturbances due to temporarily altered brain energy metabolism.

Alcohol use disorder: the role of medication in recovery - Mason BJ,; Heyser CJ (Alcohol Research, 2021)
The misuse of alcohol in the United States continues to take a large toll on society, resulting in the deaths of about 88,000 Americans per year. Moreover, it is estimated that nearly 14.6 million Americans currently meet diagnostic criteria for current alcohol use disorder (AUD). However, very few individuals receive treatment, with an even smaller portion receiving medications approved by the U.S. Food and Drug Administration (FDA) for the treatment of AUD, despite scientifically rigorous evidence showing the benefits of combining medication approved for treating AUD with evidence-based behavioral therapy. These benefits include higher rates of abstinence and less risk of relapse to heavy drinking, with associated improvements in medical and mental health and in quality of life. This review provides an overview of FDA-approved medications and “off-label” drugs for the treatment of AUD. The article emphasizes that AUD medical advice and prescription recommendations should come from professionals with training in the treatment of AUD and that treatment plans should consider medication in conjunction with evidence-based behavioral therapy. Finally, this review notes the limited number of medications available and the continued need for the development of new pharmacotherapies to optimize AUD recovery goals

Allele-specific expression and high-throughput reporter assay reveal functional genetic variants associated with alcohol use disorders. - Rao X,; Thapa KS,; Chen AB,; Lin H,; Gao H,; Reiter JL,; Hargreaves KA,; Ipe J,; Lai D,; Xuei X,; Wang Y,; Gu H,; et al. (Molecular psychiatry, 2021)
Genome-wide association studies (GWAS) of complex traits, such as alcohol use disorders (AUD), usually identify variants in non-coding regions and cannot by themselves distinguish whether the associated variants are functional or in linkage disequilibrium with the functional variants. Transcriptome studies can identify genes whose expression differs between alcoholics and controls. To test which variants associated with AUD may cause expression differences, we integrated data from deep RNA-seq and GWAS of four postmortem brain regions from 30 subjects with AUD and 30 controls to analyze allele-specific expression (ASE). We identified 88 genes with differential ASE in subjects with AUD compared to controls. Next, to test one potential mechanism contributing to the differential ASE, we analyzed single nucleotide polymorphisms (SNPs) in the 3' untranslated regions (3'UTR) of these genes. Of the 88 genes with differential ASE, 61 genes contained 437 SNPs in the 3'UTR with at least one heterozygote among the subjects studied. Using a modified PASSPORT-seq (parallel assessment of polymorphisms in miRNA target-sites by sequencing) assay, we identified 25 SNPs that affected RNA levels in a consistent manner in two neuroblastoma cell lines, SH-SY5Y and SK-N-BE(2). Many of these SNPs are in binding sites of miRNAs and RNA-binding proteins, indicating that these SNPs are likely causal variants of AUD-associated differential ASE. In sum, we demonstrate that a combination of computational and experimental approaches provides a powerful strategy to uncover functionally relevant variants associated with the risk for AUD.

Attenuated cerebral blood flow in frontolimbic and insular cortices in alcohol use disorder: relation to working memory - Sullivan E,; Zhao Q; Pohl K,; Zahr N,; Pfefferbaum A, (J Psychiatr Res, 2021)
Chronic, excessive alcohol consumption is associated with cerebrovascular hypoperfusion, which has the potential to interfere with cognitive processes. Magnetic resonance pulsed continuous arterial spin labeling (PCASL) provides a noninvasive approach for measuring regional cerebral blood flow (CBF) and was used to study 24 men and women with Alcohol Use Disorder (AUD) and 20 age- and sex-matched controls. Two analysis approaches tested group differences: a data-driven, regionally-free method to test for group differences on a voxel-by-voxel basis and a region of interest (ROI) approach, which focused quantification on atlas-determined brain structures. Whole-brain, voxel-wise quantification identified low AUD-related cerebral perfusion in large volumes of medial frontal and cingulate cortices. The ROI analysis also identified lower CBF in the AUD group relative to the control group in medial frontal, anterior/middle cingulate, insular, and hippocampal/amygdala ROIs. Further, years of AUD diagnosis negatively correlated with temporal cortical CBF, and scores on an alcohol withdrawal scale negatively correlated with posterior cingulate and occipital gray matter CBF. Regional volume deficits did not account for AUD CBF deficits. Functional relevance of attenuated regional CBF in the AUD group emerged with positive correlations between episodic working memory test scores and anterior/middle cingulum, insula, and thalamus CBF. The frontolimbic and insular cortical neuroconstellation with dampened perfusion suggests a mechanism of dysfunction associated with these brain regions in AUD. Keywords: ASL; Alcohol; Cerebral blood flow; Perfusion; Working memory.

Binge-like ethanol drinking increases Otx2, Wnt1, and Mdk gene expression in the ventral tegmental area of adult mice - Coles C,; Lasek AW, (Neurosci Insights, 2021)
Alcohol use disorder is associated with pathophysiological changes in the dopaminergic system. Orthodenticle homeobox 2 (OTX2) is a transcription factor important for the development of dopaminergic neurons residing in the ventral tegmental area (VTA), a critical region of the brain involved in drug reinforcement. Previous studies have demonstrated that ethanol exposure during embryonic development reduces Otx2 mRNA levels in the central nervous system. We hypothesized that levels of OTX2 would be altered by binge-like ethanol consumption in adult animals. To test this, Otx2 mRNA and protein levels in the mouse VTA were measured by quantitative real-time PCR and western blotting, respectively, after mice drank ethanol for 4 days in a procedure that elicits binge levels of ethanol consumption (drinking in the dark). Expression of known and putative OTX2 transcriptional target genes (Sema3c, Wnt1, and Mdk) were also measured in the VTA after ethanol drinking. Otx2 mRNA and protein levels were elevated in the VTA 24 hours after the fourth drinking session and there was a corresponding increase in the expression of Mdk transcript. Interestingly, Wnt1 transcript was elevated in the VTA immediately after the fourth drinking session but returned to control levels 24 hours later. We next investigated if viral-mediated reduction of Otx2 in the mouse VTA would alter ethanol or sucrose intake. Lentiviral vectors expressing a shRNA targeting Otx2 or a control shRNA were injected into the VTA and mice were tested in the drinking in the dark protocol for ethanol and sucrose drinking. Reducing levels of OTX2 in the VTA did not alter ethanol or sucrose consumption. One limitation is that the extent of OTX2 reduction may not have been sufficient. Although OTX2 in the VTA may not play a role in binge-like drinking in adult mice, OTX2 could contribute to ethanol-induced transcriptional changes in this region.

Cortical astrocytes regulate ethanol consumption and intoxication in mice. Neuropsychopharmacology. - Erickson EK,; Da Costa AJ,; Mason SC,; Blednov YA,; Mayfield RD; Harris RA (Neuropsychopharmacology, 2021)
Astrocytes are fundamental building blocks of the central nervous system. Their dysfunction has been implicated in many psychiatric disorders, including alcohol use disorder, yet our understanding of their functional role in ethanol intoxication and consumption is very limited. Astrocytes regulate behavior through multiple intracellular signaling pathways, including G-protein coupled-receptor (GPCR)-mediated calcium signals. To test the hypothesis that GPCR-induced calcium signaling is also involved in the behavioral effects of ethanol, we expressed astrocyte-specific excitatory DREADDs in the prefrontal cortex (PFC) of mice. Activating Gq-GPCR signaling in PFC astrocytes increased drinking in ethanol-naïve mice, but not in mice with a history of ethanol drinking. In contrast, reducing calcium signaling with an astrocyte-specific calcium extruder reduced ethanol intake. Cortical astrocyte calcium signaling also altered the acute stimulatory and sedative-hypnotic effects of ethanol. Astrocyte-specific Gq-DREADD activation increased both the locomotor-activating effects of low dose ethanol and the sedative-hypnotic effects of a high dose, while reduced astrocyte calcium signaling diminished sensitivity to the hypnotic effects. In addition, we found that adenosine A1 receptors were required for astrocyte calcium activation to increase ethanol sedation. These results support integral roles for PFC astrocytes in the behavioral actions of ethanol that are due, at least in part, to adenosine receptor activation.

Deletion of Tlr3 reduces acute tolerance to alcohol and alcohol consumption in the intermittent access procedure in male mice. - Blednov YA,; Da Costa A,; Mayfield J,; Harris RA; Messing RO, (Addict Biology, 2021)
Pharmacological studies implicate toll‐like receptor 3 (TLR3) signaling in alcohol drinking. We examined the role of TLR3 in behavioral responses to alcohol and GABAergic drugs by studying Tlr3 −/− mice. Because of opposing signaling between TLR3 and MyD88 pathways, we also evaluated Myd88 −/− mice. Ethanol consumption and preference decreased in male but not in female Tlr3 −/− mice during two‐bottle choice every‐other‐day (2BC‐EOD) drinking. There were no genotype differences in either sex during continuous or limited‐access drinking. Null mutations in Tlr3 or Myd88 did not alter conditioned taste aversion to alcohol and had small or no effects on conditioned place preference. The Tlr3 null mutation did not alter acute alcohol withdrawal. Male, but not female, Tlr3 −/− mice took longer than wild‐type littermates to recover from ataxia by ethanol or diazepam and longer to recover from sedative‐hypnotic effects of ethanol or gaboxadol, indicating regulation of GABAergic signaling by TLR3. Acute functional tolerance (AFT) to alcohol‐induced ataxia was decreased in Tlr3 −/− mice but was increased in Myd88 −/− mice. Thus, MyD88 and TLR3 pathways coordinately regulate alcohol consumption and tolerance to intoxicating doses of alcohol and GABAergic drugs. Despite similar alcohol metabolism and similar amounts of total alcohol consumed during 2BC and 2BC‐EOD procedures in C57BL/6J mice, only 2BC‐EOD drinking induced tolerance to alcohol‐induced ataxia. Ataxia recovery was inversely correlated with level of drinking in wild‐type and Tlr3 −/− littermates. Thus, deleting Tlr3 reduces alcohol consumption by reducing AFT to alcohol and not by altering tolerance induced by 2BC‐EOD drinking.

Deletion of Tlr3 reduces acute tolerance to alcohol and alcohol consumption in the intermittent access procedure in male mice - Blednov YA,; Da Costa A,; Mayfield J,; Harris RA; Messing RO. (Addict Biol, 2021)
Pharmacological studies implicate toll-like receptor 3 (TLR3) signaling in alcohol drinking. We examined the role of TLR3 in behavioral responses to alcohol and GABAergic drugs by studying Tlr3 -/- mice. Because of opposing signaling between TLR3 and MyD88 pathways, we also evaluated Myd88 -/- mice. Ethanol consumption and preference decreased in male but not in female Tlr3 -/- mice during two-bottle choice every-other-day (2BC-EOD) drinking. There were no genotype differences in either sex during continuous or limited-access drinking. Null mutations in Tlr3 or Myd88 did not alter conditioned taste aversion to alcohol and had small or no effects on conditioned place preference. The Tlr3 null mutation did not alter acute alcohol withdrawal. Male, but not female, Tlr3 -/- mice took longer than wild-type littermates to recover from ataxia by ethanol or diazepam and longer to recover from sedative-hypnotic effects of ethanol or gaboxadol, indicating regulation of GABAergic signaling by TLR3. Acute functional tolerance (AFT) to alcohol-induced ataxia was decreased in Tlr3 -/- mice but was increased in Myd88 -/- mice. Thus, MyD88 and TLR3 pathways coordinately regulate alcohol consumption and tolerance to intoxicating doses of alcohol and GABAergic drugs. Despite similar alcohol metabolism and similar amounts of total alcohol consumed during 2BC and 2BC-EOD procedures in C57BL/6J mice, only 2BC-EOD drinking induced tolerance to alcohol-induced ataxia. Ataxia recovery was inversely correlated with level of drinking in wild-type and Tlr3 -/- littermates. Thus, deleting Tlr3 reduces alcohol consumption by reducing AFT to alcohol and not by altering tolerance induced by 2BC-EOD drinking. Keywords: MyD88; TLR3; acute tolerance; ethanol consumption; knockout mice; rotarod ataxia.

Effect of chronic ethanol consumption in rhesus macaques on the nucleus accumbens core transcriptome - Walter N,; Cervera-Juanes R,; Zheng C,; Darakjian P,; Lockwood D,; Cuzon-Carlson V,; Ray K,; Fei S,; Conrad D,; Searles R,; Grant K,; Hitzemann R, (Addiction Biology, 2021)
The nucleus accumbens core (NAcc) has been repeatedly demonstrated to be a key component of the circuitry associated with excessive ethanol consumption. Previous studies have illustrated that in a nonhuman primate (NHP) model of chronic ethanol consumption, there is significant epigenetic remodeling of the NAcc. In the current study, RNA-Seq was used to examine genome-wide gene expression in eight each of control, low/binge (LD*), and high/very high (HD*) rhesus macaque drinkers. Using an FDR < 0.05, zero genes were significantly differentially expressed (DE) between LD* and controls, six genes between HD* and LD*, and 734 genes between HD* and controls. Focusing on HD* versus control DE genes, the upregulated genes (N = 366) were enriched in genes with annotations associated with signal recognition particle (SRP)-dependent co-translational protein targeting to membrane (FDR < 3 × 10−59), structural constituent of ribosome (FDR < 3 × 10−47), and ribosomal subunit (FDR < 5 × 10−48). Downregulated genes (N = 363) were enriched in annotations associated with behavior (FDR < 2 × 10−4), membrane organization (FDR < 1 × 10−4), inorganic cation transmembrane transporter activity (FDR < 2 × 10−3), synapse part (FDR < 4 × 10−10), glutamatergic synapse (FDR < 1 × 10−6), and GABAergic synapse (FDR < 6 × 10−4). Ingenuity Pathway Analysis (IPA) revealed that EIF2 signaling and mTOR pathways were significantly upregulated in HD* animals (FDR < 3 × 10−33 and <2 × 10−16, respectively). Overall, the data supported our working hypothesis; excessive consumption would be associated with transcriptional differences in GABA/glutamate-related genes.

Effect of Glucocorticoid Receptor Antagonism on Alcohol Self-Administration in Genetically-Selected Marchigian Sardinian Alcohol-Preferring and Non-Preferring Wistar Rats - Benvenuti F,; Cannella N,; Stopponi S,; Soverchia L,; Ubaldi M,; Lunerti V,; Vozella V,; Cruz B,; Roberto M; Ciccocioppo R, (Int J Mol Sci, 2021)
Alcoholism is a chronically relapsing disorder characterized by high alcohol intake and a negative emotional state during abstinence, which contributes to excessive drinking and susceptibility to relapse. Stress, dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis and alterations in glucocorticoid receptor (GR) function have been linked to transition from recreational consumption to alcohol use disorder (AUD). Here, we investigated the effect of pharmacological antagonisms of GR on alcohol self-administration (SA) using male and female Wistar and Marchigian Sardinian alcohol-preferring (msP) rats, a rodent line genetically selected for excessive alcohol drinking and highly sensitive to stress. Animals were trained to self-administer 10% (v/v) alcohol. Once a stable alcohol SA baseline was reached, we tested the effect of the GR antagonists mifepristone (0.0, 10, 30 and 60 mg/kg; i.p.) and CORT113176 (0.0, 10, 30 and 60 mg/kg) on alcohol SA. To evaluate whether the effects of the two compounds were specific for alcohol, the two drugs were tested on a similar saccharin SA regimen. Finally, basal blood corticosterone (CORT) levels before and after alcohol SA were determined. Systemic injection with mifepristone dose-dependently reduced alcohol SA in male and female Wistars but not in msPs. Administration of CORT113176 decreased alcohol SA in male and female Wistars as well as in female msPs but not in male msP rats. At the highest dose, mifepristone also reduced saccharin SA in male Wistars and female msPs, suggesting the occurrence of some nonspecific effects at 60 mg/kg of the drug. Similarly, the highest dose of CORT113176 (60 mg/kg) decreased saccharin intake in male Wistars. Analysis of CORT levels revealed that females of both rat lines had higher blood levels of CORT compared to males. Alcohol consumption reduced CORT in females but not in males. Overall, these findings indicate that selective blockade of GR selectively reduces alcohol SA, and genetically selected msP rats are less sensitive to this pharmacological manipulation compared to heterogeneous Wistars. Moreover, results suggest sex differences in response to GR antagonism and the ability of alcohol to regulate GR transmission. Keywords: alcohol preferring rats; alcohol self-administration; alcohol use disorder; glucocorticoids; mifepristone; stress.

Epigenetic and non-coding regulation of alcohol abuse and addiction. - Farris SP,; Mayfield RD. (International review of neurobiology, 2021)
Alcohol use disorder is a chronic debilitated condition adversely affecting the lives of millions of individuals throughout the modern world. Individuals suffering from an alcohol use disorder diagnosis frequently have serious cooccurring conditions, which often further exacerbates problematic drinking behavior. Comprehending the biochemical processes underlying the progression and perpetuation of disease is essential for mitigating maladaptive behavior in order to restore both physiological and psychological health. The range of cellular and biological systems contributing to, and affected by, alcohol use disorder and other comorbid disorders necessitates a fundamental grasp of intricate functional relationships that govern molecular biology. Epigenetic factors are recognized as essential mediators of cellular behavior, orchestrating a symphony of gene expression changes within multicellular environments that are ultimately responsible for directing human behavior. Understanding the epigenetic and transcriptional regulatory mechanisms involved in the pathogenesis of disease is important for improving available pharmacotherapies and reducing the incidence of alcohol abuse and cooccurring conditions. Keywords: Addiction; Alcohol abuse; Epigenetics; Gene expression; Non-coding RNA.

Epigenetic mechanisms underlying stress-induced depression - Martins de Carvalho L,; Chen WY; Satta R, Hilderbrand ER, Lasek AW (Int Rev Neurobiol, 2021)
Stressful life events are a major contributor to the development of major depressive disorder. Environmental perturbations like stress change gene expression in the brain, leading to altered behavior. Gene expression is ultimately regulated by chromatin structure and the epigenetic modifications of DNA and the histone proteins that make up chromatin. Studies over the past two decades have demonstrated that stress alters the epigenetic landscape in several brain regions relevant for depressive-like behavior in rodents. This chapter will discuss epigenetic mechanisms of brain histone acetylation, histone methylation, and DNA methylation that contribute to adult stress-induced depressive-like behavior in rodents. Several biological themes have emerged from the examination of the brain transcriptome after stress such as alterations in the neuroimmune response, neurotrophic factors, and synaptic structure. The epigenetic mechanisms regulating these processes will be highlighted. Finally, pharmacological and genetic manipulations of epigenetic enzymes in rodent models of depression will be discussed as these approaches have demonstrated the ability to reverse stress-induced depressive-like behaviors and provide

The escalation in ethanol consumption following chronic intermittent ethanol exposure is blunted in mice expressing ethanol-resistant GluN1 or GluN2A NMDA receptor subunits. - Zamudio PA,; Gioia DA,; Lopez M,; Homanics GE,; Woodward JJ (Psychopharmacology, 2021)
N-Methyl-D-aspartate receptors (NMDARs) are glutamate-gated ion channels essential for glutamatergic transmission and plasticity. NMDARs are inhibited by acute ethanol and undergo brain region-specific adaptations after chronic alcohol exposure. In previous studies, we reported that knock-in mice expressing ethanol-insensitive GluN1 or GluN2A NMDAR subunits display altered behavioral responses to acute ethanol and genotype-dependent changes in drinking using protocols that do not produce dependence. A key unanswered question is whether the intrinsic ethanol sensitivity of NMDARs also plays a role in determining behavioral adaptations that accompany the development of dependence. To test this, we exposed mice to repeated cycles of chronic intermittent ethanol (CIE) vapor known to produce a robust escalation in ethanol consumption and preference. As expected, wild-type mice showed a significant increase from baseline in ethanol consumption and preference after each of the four weekly CIE cycles. In contrast, ethanol consumption in male GluN2A(A825W) mice was unchanged following cycles 1, 2, and 4 of CIE with a modest increase appearing after cycle 3. Wild-type and GluN2A(A825W) female mice did not show a clear or consistent escalation in ethanol consumption or preference following CIE treatment. In male GluN1(F639A) mice, the increase in ethanol consumption observed with their wild-type littermates was delayed until later cycles of exposure. These results suggest that the acute ethanol sensitivity of NMDARs especially those containing the GluN2A subunit may be a critical factor in the escalation of ethanol intake in alcohol dependence.

Ethanol-related behaviors in mouse lines selectively bred for drinking to intoxication - Jensen BE,; Townsley KG,; Grigsby KB,; Metten P,; Chand M,; Uzoekwe M,; Tran A,; Firsick E, (Brain Sciences, 2021)
Alcohol use disorder (AUD) is a devastating psychiatric disorder that has significant wide-reaching effects on individuals and society. Selectively bred mouse lines are an effective means of exploring the genetic and neuronal mechanisms underlying AUD and such studies are translationally important for identifying treatment options. Here, we report on behavioral characterization of two replicate lines of mice that drink to intoxication, the High Drinking in the Dark (HDID)-1 and -2 mice, which have been selectively bred (20+ generations) for the primary phenotype of reaching high blood alcohol levels (BALs) during the drinking in the dark (DID) task, a binge-like drinking assay. Along with their genetically heterogenous progenitor line, Hs/Npt, we tested these mice on: DID and drinking in the light (DIL); temporal drinking patterns; ethanol sensitivity, through loss of righting reflex (LORR); and operant self-administration, including fixed ratio (FR1), fixed ratio 3:1 (FR3), extinction/reinstatement, and progressive ratio (PR). All mice consumed more ethanol during the dark than the light and both HDID lines consumed more ethanol than Hs/Npt during DIL and DID. In the dark, we found that the HDID lines achieved high blood alcohol levels early into a drinking session, suggesting that they exhibit front loading like drinking behavior in the absence of the chronicity usually required for such behavior. Surprisingly, HDID-1 (female and male) and HDID-2 (male) mice were more sensitive to the intoxicating effects of ethanol during the dark (as determined by LORR), while Hs/Npt (female and male) and HDID-2 (female) mice appeared less sensitive. We observed lower HDID-1 ethanol intake compared to either HDID-2 or Hs/Npt during operant ethanol self-administration. There were no genotype differences for either progressive ratio responding, or cue-induced ethanol reinstatement, though the latter is complicated by a lack of extinguished responding behavior. Taken together, these findings suggest that genes affecting one AUD-related behavior do not necessarily affect other AUD-related behaviors. Moreover, these findings highlight that alcohol-related behaviors can also differ between lines selectively bred for the same phenotype, and even between sexes within those same line. Keywords: drinking in the dark; ethanol; mice; operant self-administration; selected lines; sensitivity to ethanol.

Exposure to drugs of abuse induce effects that persist across generations - Baratta AM,; Rathod RS,; Plasil SL,; Seth A,; Homanics GE, (Int Rev Neurobiol, 2021)
Substance use disorders are highly prevalent and continue to be one of the leading causes of disability in the world. Notably, not all people who use addictive drugs develop a substance use disorder. Although substance use disorders are highly heritable, patterns of inheritance cannot be explained purely by Mendelian genetic mechanisms. Vulnerability to developing drug addiction depends on the interplay between genetics and environment. Additionally, evidence from the past decade has pointed to the role of epigenetic inheritance in drug addiction. This emerging field focuses on how environmental perturbations, including exposure to addictive drugs, induce epigenetic modifications that are transmitted to the embryo at fertilization and modify developmental gene expression programs to ultimately impact subsequent generations. This chapter highlights intergenerational and transgenerational phenotypes in offspring following a history of parental drug exposure. Special attention is paid to parental preconception exposure studies of five drugs of abuse (alcohol, cocaine, nicotine, cannabinoids, and opiates) and associated behavioral and physiological outcomes in offspring. The highlighted studies demonstrate that parental exposure to drugs of abuse has enduring effects that persist into subsequent generations. Understanding the contribution of epigenetic inheritance in drug addiction may provide clues for better treatments and therapies for substance use disorders.

Glucocorticoid receptor antagonist mifepristone does not alter innate anxiety-like behavior in genetically-selected Marchigian Sardinian (msP) rats - Vozella V,; Cruz B,; Natividad LA,; Benvenuti F,; Cannella N,; Edwards S,; Zorrilla EP,; Ciccocioppo R,; M., Roberto (International Journal of Molecular Sciences, 2021)
Marchigian Sardinian alcohol-preferring (msP) rats serve as a unique model of heightened alcohol preference and anxiety disorders. Their innate enhanced stress and poor stress-coping strategies are driven by a genetic polymorphism of the corticotropin-releasing factor receptor 1 (CRF1) in brain areas involved in glucocorticoid signaling. The activation of glucocorticoid receptors (GRs) regulates the stress response, making GRs a candidate target to treat stress and anxiety. Here, we examined whether mifepristone, a GR antagonist known to reduce alcohol drinking in dependent rats, decreases innate symptoms of anxiety in msPs. Male and female msPs were compared to non-selected Wistar counterparts across three separate behavioral tests. We assessed anxiety-like behavior via the novelty-induced hypophagia (NIH) assay. Since sleep disturbances and hyperarousal are common features of stress-related disorders, we measured sleeping patterns using the comprehensive lab monitoring system (CLAMS) and stress sensitivity using acoustic startle measures. Rats received an acute administration of vehicle or mifepristone (60 mg/kg) 90 min prior to testing on NIH, acoustic startle response, and CLAMS. Our results revealed that both male and female msPs display greater anxiety-like behaviors as well as enhanced acoustic startle responses compared to Wistar counterparts. Male msPs also displayed reduced sleeping bout duration versus Wistars, and female msPs displayed greater acoustic startle responses versus male msPs. Importantly, the enhanced anxiety-like behavior and startle responses were not reduced by mifepristone. Together, these findings suggest that increased expression of stress-related behaviors in msPs are not solely mediated by acute activation of GRs.

Hippocampal β2-GABAA receptors mediate LTP suppression by etomidate and contribute to long-lasting feedback but not feedforward inhibition of pyramidal neurons. - Figueroa AG,; Benkwitz C,; Surges G,; Kunz N,; Homanics GE,; Pearce RA (J Neurophysiol, 2021)
The general anesthetic etomidate, which acts through γ-aminobutyric acid type A (GABAA) receptors, impairs the formation of new memories under anesthesia. This study addresses the molecular and cellular mechanisms by which this occurs. Here, using a new line of genetically engineered mice carrying the GABAA receptor (GABAAR) β2-N265M mutation, we tested the roles of receptors that incorporate GABAA receptor β2 versus β3 subunits to suppression of long-term potentiation (LTP), a cellular model of learning and memory. We found that brain slices from β2-N265M mice resisted etomidate suppression of LTP, indicating that the β2-GABAARs are an essential target in this model. As these receptors are most heavily expressed by interneurons in the hippocampus, this finding supports a role for interneuron modulation in etomidate control of synaptic plasticity. Nevertheless, β2 subunits are also expressed by pyramidal neurons, so they might also contribute. Therefore, using a previously established line of β3-N265M mice, we also examined the contributions of β2- versus β3-GABAARs to GABAA,slow dendritic inhibition, because dendritic inhibition is particularly well suited to controlling synaptic plasticity. We also examined their roles in long-lasting suppression of population activity through feedforward and feedback inhibition. We found that both β2- and β3-GABAARs contribute to GABAA,slow inhibition and that both β2- and β3-GABAARs contribute to feedback inhibition, whereas only β3-GABAARs contribute to feedforward inhibition. We conclude that modulation of β2-GABAARs is essential to etomidate suppression of LTP. Furthermore, to the extent that this occurs through GABAARs on pyramidal neurons, it is through modulation of feedback inhibition. NEW & NOTEWORTHY Etomidate exerts its anesthetic actions through GABAA receptors. However, the mechanism remains unknown. Here, using a hippocampal brain slice model, we show that β2-GABAARs are essential to this effect. We also show that these receptors contribute to long-lasting dendritic inhibition in feedback but not feedforward inhibition of pyramidal neurons. These findings hold implications for understanding how anesthetics block memory formation and, more generally, how inhibitory circuits control learning and memory. Keywords: GABAA receptors; etomidate; general anesthesia; learning and memory.

IL-10 normalizes aberrant amygdala GABA transmission and reverses anxiety-like behavior and dependence-induced escalation of alcohol intake - Patel RR,; Wolfe SA,; Bajo M,; Abeynaike S,; Pahng A,; Borgonetti V,; D'Ambrosio S,; Nikzad R,; Edwards S,; Paust S; Roberts AJ,; Roberto M (Prog Neurobiol, 2021)
Alcohol elicits a neuroimmune response in the brain contributing to the development and maintenance of alcohol use disorder (AUD). While pro-inflammatory mediators initiate and drive the neuroimmune response, anti-inflammatory mediators provide an important homeostatic mechanism to limit inflammation and prevent pathological damage. However, our understanding of the role of anti-inflammatory signaling on neuronal physiology in critical addiction-related brain regions and pathological alcohol-dependence induced behaviors is limited, precluding our ability to identify promising therapeutic targets. Here, we hypothesized that chronic alcohol exposure compromises anti-inflammatory signaling in the central amygdala, a brain region implicated in anxiety and addiction, consequently perpetuating a pro-inflammatory state driving aberrant neuronal activity underlying pathological behaviors. We found that alcohol dependence alters the global brain immune landscape increasing IL-10 producing microglia and T-regulatory cells but decreasing local amygdala IL-10 levels. Amygdala IL-10 overexpression decreases anxiety-like behaviors, suggesting its local role in regulating amygdala-mediated behaviors. Mechanistically, amygdala IL-10 signaling through PI3K and p38 MAPK modulates GABA transmission directly at presynaptic terminals and indirectly through alterations in spontaneous firing. Alcohol dependence-induces neuroadaptations in IL-10 signaling leading to an overall IL-10-induced decrease in GABA transmission, which normalizes dependence-induced elevated amygdala GABA transmission. Notably, amygdala IL-10 overexpression abolishes escalation of alcohol intake, a diagnostic criterion of AUD, in dependent mice. This highlights the importance of amygdala IL-10 signaling in modulating neuronal activity and underlying anxiety-like behavior and aberrant alcohol intake, providing a new framework for therapeutic intervention.

The impact of Drinking in the Dark (DID) procedural manipulations on ethanol intake in High Drinking in the Dark (HDID) mice - Savarese AM,; Ozburn AR,; Barkley-Levenson AM,; Metten P,; Crabbe JC, (Alcohol, 2021)
The High Drinking in the Dark mouse lines (HDID-1 and HDID-2) were selectively bred to achieve high blood ethanol concentrations (BECs) in the Drinking in the Dark (DID) task, a widely used model of binge-like intake of 20% ethanol. There are several components that differentiate DID from other animal models of ethanol intake: time of day of testing, length of ethanol access, single-bottle access, and individual housing. Here, we sought to determine how some of these individual factors contribute to the high ethanol intake observed in HDID mice. HDID-1, HDID-2, and non-selected HS/NPT mice were tested in a series of DID experiments where one of the following factors was manipulated: length of ethanol access, fluid choice, number of ethanol bottles, and housing condition. We observed that (1) HDID mice achieve intoxicating BECs in DID, even when they are group-housed; (2) HDID mice continue to show elevated ethanol intake relative to HS/NPT mice during an extended access session, but this is most apparent during the first four hours of access; and (3) offering a water choice during DID prevents elevated intake in the HDID-1 mice, but not necessarily in HDID-2 mice. Together, these results suggest that the lack of choice in the DID paradigm, together with the length of ethanol access, are important factors contributing to elevated ethanol intake in the HDID mice. These results further suggest important differences between the HDID lines in response to procedural manipulations of housing condition and ethanol bottle number in the DID paradigm, highlighting the distinct characteristics that each of these lines possess, despite being selectively bred for the same phenotype.

Impaired hypothalamic feedback dysregulates brain glucocorticoid signaling in genetically-selected Marchigian Sardinian alcohol-preferring rats. - Natividad LA,; Steinman MQ,; McGinn MA,; Sureshchandra S,; Kerr TM,; Ciccocioppo R,; Messaoudi I,; Edwards S,; Roberto M (Addict Biology, 2021)
Genetically‐selected Marchigian Sardinian alcohol‐preferring (msP) rats display comorbid symptoms of increased alcohol preference and elevated anxiety‐like behavior. Heightened stress sensitivity in msPs is influenced by genetic polymorphisms of the corticotropin‐releasing factor receptor in the central nucleus of the amygdala (CeA), as well as reduced influence of anti‐stress mechanisms that normally constrain the stress response. Given this propensity for stress dysregulation, in this study, we expand on the possibility that msPs may display differences in neuroendocrine processes that normally terminate the stress response. We utilized behavioral, biochemical, and molecular assays to compare basal and restraint stress‐induced changes in the hypothalamic–pituitary–adrenal (HPA) axis of male and female msPs relative to their nonselected Wistar counterparts. The results showed that msPs display deficits in marble‐burying behavior influenced by environmental factors and procedures that modulate arousal states in a sex‐dependent manner. Whereas male msPs display evidence of dysregulated neuroendocrine function (higher adrenocorticotropic hormone levels and subthreshold reductions in corticosterone), females display restraint‐induced elevations in corticosterone levels that were persistently higher in msPs. A dexamethasone challenge reduced the circulation of these stress hormones, although the reduction in corticosterone was generally attenuated in msP versus Wistar rats. Finally, we found evidence of diminished stress‐induced glucocorticoid receptor (GR) phosphorylation in the hypothalamic paraventricular nucleus of msPs, as well as innate increases in phosphorylated GR levels in the CeA of male msPs. Collectively, these findings suggest that negative feedback processes regulating HPA responsiveness are diminished in msP rats, possibly underlying differences in the expression of anxiety‐like behaviors.

Jacobian mapping reveals converging brain substrates of disruption and repair in response to ethanol exposure and abstinence in 2 strains of rats - Zhao Q; Pohl KM; Sullivan E,; Pfefferbaum A,; Zahr NM (Alcohol Clin Exp Res, 2021)
Background: In a previous study using Jacobian mapping to evaluate the morphological effects on the brain of binge (4-day) intragastric ethanol (EtOH) on wild-type Wistar rats, we reported reversible thalamic shrinkage and lateral ventricular enlargement, but persistent superior and inferior colliculi shrinkage in response to binge EtOH treatment. Methods: Herein, we used similar voxel-based comparisons of Magnetic Resonance Images collected in EtOH-exposed relative to control animals to test the hypothesis that regardless of the intoxication protocol or the rat strain, the hippocampi, thalami, and colliculi would be affected. Results: Two experiments [binge (4-day) intragastric EtOH in Fisher 344 rats and chronic (1-month) vaporized EtOH in Wistar rats] showed similarly affected brain regions including retrosplenial and cingulate cortices, dorsal hippocampi, central and ventroposterior thalami, superior and inferior colliculi, periaqueductal gray, and corpus callosum. While most of these regions showed significant recovery, volumes of the colliculi and periaqueductal gray continued to show response to each proximal EtOH exposure but at diminished levels with repeated cycles. Conclusions: Given the high metabolic rate of these enduringly affected regions, the current findings suggest that EtOH per se may affect cellular respiration leading to brain volume deficits. Further, responsivity greatly diminished likely reflecting neuroadaptation to repeated alcohol exposure. In summary, this unbiased, in vivo-based approach demonstrating convergent brain systems responsive to 2 EtOH exposure protocols in 2 rat strains highlights regions that warrant further investigation in both animal models of alcoholism and in humans with alcohol use disorder.

Jacobian Mapping Reveals Converging Substrates of Disruption and Repair in Response to Ethanol Exposure and Abstinence in Two Strains of Rats. - Zhao Q; Pohl KM; Sullivan EV; Pfefferbaum A,; Zahr NM (Alcoholism: Clinical and Experimental Research, 2021)
Background In a previous study using Jacobian mapping to evaluate the morphological effects on the brain of binge (4‐day) intragastric ethanol (EtOH) on wild‐type Wistar rats, we reported reversible thalamic shrinkage and lateral ventricular enlargement, but persistent superior and inferior colliculi shrinkage in response to binge EtOH treatment. Methods Herein, we used similar voxel‐based comparisons of Magnetic Resonance Images collected in EtOH‐exposed relative to control animals to test the hypothesis that regardless of the intoxication protocol or the rat strain, the hippocampi, thalami, and colliculi would be affected. Results Two experiments [binge (4‐day) intragastric EtOH in Fisher 344 rats and chronic (1‐month) vaporized EtOH in Wistar rats] showed similarly affected brain regions including retrosplenial and cingulate cortices, dorsal hippocampi, central and ventroposterior thalami, superior and inferior colliculi, periaqueductal gray, and corpus callosum. While most of these regions showed significant recovery, volumes of the colliculi and periaqueductal gray continued to show response to each proximal EtOH exposure but at diminished levels with repeated cycles. Conclusions Given the high metabolic rate of these enduringly affected regions, the current findings suggest that EtOH per se may affect cellular respiration leading to brain volume deficits. Further, responsivity greatly diminished likely reflecting neuroadaptation to repeated alcohol exposure. In summary, this unbiased, in vivo‐based approach demonstrating convergent brain systems responsive to 2 EtOH exposure protocols in 2 rat strains highlights regions that warrant further investigation in both animal models of alcoholism and in humans with alcohol use disorder.

A Kalirin missense mutation enhances dendritic RhoA signaling and leads to regression of cortical dendritic arbors across development - Grubisha MJ,; Sun T,; Eisenman L,; Erickson SL; Chou SY,; Helmer CD,; Trudgen MT; Ding Y,; Homanics GE,; Penzes P,; Wills ZP,; Sweet RA. (Proc Natl Acad Sci U S A, 2021)
Normally, dendritic size is established prior to adolescence and then remains relatively constant into adulthood due to a homeostatic balance between growth and retraction pathways. However, schizophrenia is characterized by accelerated reductions of cerebral cortex gray matter volume and onset of clinical symptoms during adolescence, with reductions in layer 3 pyramidal neuron dendritic length, complexity, and spine density identified in multiple cortical regions postmortem. Nogo receptor 1 (NGR1) activation of the GTPase RhoA is a major pathway restricting dendritic growth in the cerebral cortex. We show that the NGR1 pathway is stimulated by OMGp and requires the Rho guanine nucleotide exchange factor Kalirin-9 (KAL9). Using a genetically encoded RhoA sensor, we demonstrate that a naturally occurring missense mutation in Kalrn, KAL-PT, that was identified in a schizophrenia cohort, confers enhanced RhoA activitation in neuronal dendrites compared to wild-type KAL. In mice containing this missense mutation at the endogenous locus, there is an adolescent-onset reduction in dendritic length and complexity of layer 3 pyramidal neurons in the primary auditory cortex. Spine density per unit length of dendrite is unaffected. Early adult mice with these structural deficits exhibited impaired detection of short gap durations. These findings provide a neuropsychiatric model of disease capturing how a mild genetic vulnerability may interact with normal developmental processes such that pathology only emerges around adolescence. This interplay between genetic susceptibility and normal adolescent development, both of which possess inherent individual variability, may contribute to heterogeneity seen in phenotypes in human neuropsychiatric disease. Keywords: Kalirin; NGR1; adolescence; dendrite.

A long non-coding RNA (Lrap) modulates brain gene expression and levels of alcohol consumption in rats. - Saba LM,; Hoffman PL,; Homanics GE,; Mahaffey S,; Daulatabad SV,; Janga SC,; Tabakoff B (Genes, Brain and Behavior, 2021)
LncRNAs are important regulators of quantitative and qualitative features of the transcriptome. We have used QTL and other statistical analyses to identify a gene coexpression module associated with alcohol consumption. The “hub gene” of this module, Lrap (Long non‐coding RNA for alcohol preference), was an unannotated transcript resembling a lncRNA. We used partial correlation analyses to establish that Lrap is a major contributor to the integrity of the coexpression module. Using CRISPR/Cas9 technology, we disrupted an exon of Lrap in Wistar rats. Measures of alcohol consumption in wild type, heterozygous and knockout rats showed that disruption of Lrap produced increases in alcohol consumption/alcohol preference. The disruption of Lrap also produced changes in expression of over 700 other transcripts. Furthermore, it became apparent that Lrap may have a function in alternative splicing of the affected transcripts. The GO category of “Response to Ethanol” emerged as one of the top candidates in an enrichment analysis of the differentially expressed transcripts. We validate the role of Lrap as a mediator of alcohol consumption by rats, and also implicate Lrap as a modifier of the expression and splicing of a large number of brain transcripts. A defined subset of these transcripts significantly impacts alcohol consumption by rats (and possibly humans). Our work shows the pleiotropic nature of non‐coding elements of the genome, the power of network analysis in identifying the critical elements influencing phenotypes, and the fact that not all changes produced by genetic editing are critical for the concomitant changes in phenotype.

Mapping the living mouse brain neural architecture: strain-specific patterns of brain structural and functional connectivity - Karatas M,; Noblet V,; Nasseef MT,; Bienert T,; Reisert M,; Hennig J,; Yalcin I,; Kieffer BL,; von Elverfeldt D,; Harsan LA, (Brain Struct Funct, 2021)
Mapping the structural and functional brain connectivity fingerprints became an essential approach in neurology and experimental neuroscience because network properties can underlie behavioral phenotypes. In mouse models, revealing strain related patterns of brain wiring have a tremendous importance, since these animals are used to answer questions related to neurological or neuropsychiatric disorders. C57BL/6 and BALB/cJ inbred strains are primary “genetic backgrounds” for brain disease modelling and for testing therapeutic approaches. Nevertheless, extensive literature describes basal differences in the behavioral, neuroanatomical and neurochemical profiles of the two strains, which raises the question whether the observed effects are pathology specific or depend on the genetic background. Here we performed a systematic comparative exploration of brain structure and function of C57BL/6 and BALB/cJ mice via Magnetic Resonance Imaging (MRI). We combined voxel-based morphometry (VBM), diffusion MRI and high resolution fiber mapping (hrFM) and resting state functional MRI (rs-fMRI) and depicted brain-wide dissimilarities in the morphology and “connectome” features in the two strains. Particularly C57BL/6 animals show bigger and denser frontal cortical areas, cortico-striatal tracts and thalamic and midbrain pathways, and higher density of fibers in the genu and splenium of the corpus callosum. These features are fairly reflected in the functional connectograms that emphasize differences in “hubness”, frontal cortical and basal forbrain connectivity. We demonstrate strongly divergent reward-aversion circuitry patterns and some variations of the default mode network features. Inter-hemispherical functional connectivity showed flexibility and adjustment regarding the structural patterns in a strain specific manner. We further provide high-resolution tractograms illustrating also inter-individual variability across inter-hemispherical callosal pathways in the BALB/cJ strain.

Memory impairment in alcohol use disorder is associated with regional frontal brain volumes - Fama R,; Le Berre AP,; Sassoon SA,; Zahr NM; Pohl KM; Pfefferbaum A,; Sullivan EV. (Drug Alcohol Depend, 2021)
Background: Episodic memory deficits occur in alcohol use disorder (AUD), but their anatomical substrates remain in question. Although persistent memory impairment is classically associated with limbic circuitry disruption, learning and retrieval of new information also relies on frontal systems. Despite AUD vulnerability of frontal lobe integrity, relations between frontal regions and memory processes have been under-appreciated. Methods: Participants included 91 AUD (49 with a drug diagnosis history) and 36 controls. Verbal and visual episodic memory scores were age- and education-corrected. Structural magnetic resonance imaging (MRI) data yielded regional frontal lobe (precentral, superior, orbital, middle, inferior, supplemental motor, and medial) and total hippocampal volumes. Results: AUD were impaired on all memory scores and had smaller precentral frontal and hippocampal volumes than controls. Orbital, superior, and inferior frontal volumes and lifetime alcohol consumption were independent predictors of episodic memory in AUD. Selectivity was established with a double dissociation, where orbital frontal volume predicted verbal but not visual memory, whereas inferior frontal volumes predicted visual but not verbal memory. Further, superior frontal volumes predicted verbal memory in AUD alone, whereas orbital frontal volumes predicted verbal memory in AUD+drug abuse history. Conclusions: Selective relations among frontal subregions and episodic memory processes highlight the relevance of extra-limbic regions in mnemonic processes in AUD. Memory deficits resulting from frontal dysfunction, unlike the episodic memory impairment associated with limbic dysfunction, may be more amenable to recovery with cessation or reduction of alcohol misuse and may partially explain the heterogeneity in episodic memory abilities in AUD. Keywords: Alcohol; Drug abuse; Episodic memory; Frontal volumes; MRI; Orbitofrontal. Copyright © 2021 Elsevier B.V. All rights reserved.

Microglia depletion and alcohol: Transcriptome and behavioral profiles. - Warden AS,; Triplett TA,; Lyu A,; Grantham EK,; Azzam MM,; Da Costa A,; Mason S,; Blednov YA,; Ehrlich LIR,; Mayfield RD; Harris RA (Addict Biology, 2021)
Alcohol abuse induces changes in microglia morphology and immune function, but whether microglia initiate or simply amplify the harmful effects of alcohol exposure is still a matter of debate. Here, we determine microglia function in acute and voluntary drinking behaviors using a colony‐stimulating factor 1 receptor inhibitor (PLX5622). We show that microglia depletion does not alter the sedative or hypnotic effects of acute intoxication. Microglia depletion also does not change the escalation or maintenance of chronic voluntary alcohol consumption. Transcriptomic analysis revealed that although many immune genes have been implicated in alcohol abuse, downregulation of microglia genes does not necessitate changes in alcohol intake. Instead, microglia depletion and chronic alcohol result in compensatory upregulation of alcohol‐responsive, reactive astrocyte genes, indicating astrocytes may play a role in regulation of these alcohol behaviors. Taken together, our behavioral and transcriptional data indicate that microglia are not the primary effector cell responsible for regulation of acute and voluntary alcohol behaviors. Because microglia depletion did not regulate acute or voluntary alcohol behaviors, we hypothesized that these doses were insufficient to activate microglia and recruit them to an effector phenotype. Therefore, we used a model of repeated immune activation using polyinosinic:polycytidylic acid (poly(I:C)) to activate microglia. Microglia depletion blocked poly(I:C)‐induced escalations in alcohol intake, indicating microglia regulate drinking behaviors with sufficient immune activation. By testing the functional role of microglia in alcohol behaviors, we provide insight into when microglia are causal and when they are consequential for the transition from alcohol use to dependence.

Preliminary evidence for a relationship between elevated plasma TNFα and smaller subcortical white matter volume in HCV infection irrespective of HIV or AUD comorbidity - Zahr NM; Pohl KM; Kwong AJ,; Sullivan EV; Pfefferbaum A, (Int J Mol Sci, 2021)
Classical inflammation in response to bacterial, parasitic, or viral infections such as HIV includes local recruitment of neutrophils and macrophages and the production of proinflammatory cytokines and chemokines. Proposed biomarkers of organ integrity in Alcohol Use Disorders (AUD) include elevations in peripheral plasma levels of proinflammatory proteins. In testing this proposal, previous work included a group of human immunodeficiency virus (HIV)-infected individuals as positive controls and identified elevations in the soluble proteins TNFα and IP10; these cytokines were only elevated in AUD individuals seropositive for hepatitis C infection (HCV). The current observational, cross-sectional study evaluated whether higher levels of these proinflammatory cytokines would be associated with compromised brain integrity. Soluble protein levels were quantified in 86 healthy controls, 132 individuals with AUD, 54 individuals seropositive for HIV, and 49 individuals with AUD and HIV. Among the patient groups, HCV was present in 24 of the individuals with AUD, 13 individuals with HIV, and 20 of the individuals in the comorbid AUD and HIV group. Soluble protein levels were correlated to regional brain volumes as quantified with structural magnetic resonance imaging (MRI). In addition to higher levels of TNFα and IP10 in the 2 HIV groups and the HCV-seropositive AUD group, this study identified lower levels of IL1β in the 3 patient groups relative to the control group. Only TNFα, however, showed a relationship with brain integrity: in HCV or HIV infection, higher peripheral levels of TNFα correlated with smaller subcortical white matter volume. These preliminary results highlight the privileged status of TNFα on brain integrity in the context of infection.

Reduced sedation and increased ethanol consumption in knock-in mice expressing an ethanol insensitive alpha 2 subunit of the glycine receptor. - Gallegos S,; San Martin L,; Araya A,; Lovinger DM; Homanics GE,; Aguayo LG (Neuropsychopharmacology, 2021)
Previous studies have shown the presence of several subunits of the inhibitory glycine receptor (GlyR) in the reward system, specifically in medium spiny neurons (MSNs) of the nucleus Accumbens (nAc). It was suggested that GlyR α1 subunits regulate nAc excitability and ethanol consumption. However, little is known about the role of the α2 subunit in the adult brain since it is a subunit highly expressed during early brain development. In this study, we used genetically modified mice with a mutation (KR389–390AA) in the intracellular loop of the GlyR α2 subunit which results in a heteromeric α2β receptor that is insensitive to ethanol. Using this mouse model denoted knock-in α2 (KI α2), our electrophysiological studies showed that neurons in the adult nAc expressed functional KI GlyRs that were rather insensitive to ethanol when compared with WT GlyRs. In behavioral tests, the KI α2 mice did not show any difference in basal motor coordination, locomotor activity, or conditioned place preference compared with WT littermate controls. In terms of ethanol response, KI α2 male mice recovered faster from the administration of ataxic and sedative doses of ethanol. Furthermore, KI α2 mice consumed higher amounts of ethanol in the first days of the drinking in the dark protocol, as compared with WT mice. These results show that the α2 subunit is important for the potentiation of GlyRs in the adult brain and this might result in reduced sedation and increased ethanol consumption.

The Role of the Central Amygdala in Alcohol Dependence. - Roberto M; Kirson D,; Khom S, (Cold Spring Harb Perspect Med, 2021)
Alcohol dependence is a chronically relapsing disorder characterized by compulsive drug-seeking and drug-taking, loss of control in limiting intake, and the emergence of a withdrawal syndrome in the absence of the drug. Accumulating evidence suggests an important role for synaptic transmission in the central nucleus of the amygdala (CeA) in mediating alcohol-related behaviors and neuroadaptive mechanisms associated with alcohol dependence. Acute alcohol facilitates γ-aminobutyric acid (GABA)ergic transmission in the CeA via both pre- and postsynaptic mechanisms, and chronic alcohol increases baseline GABAergic transmission. Acute alcohol inhibits glutamatergic transmission via effects at N-methyl-d-aspartate (NMDA) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in the CeA, whereas chronic alcohol up-regulates NMDA receptor (NMDAR)-mediated transmission. Pro- (e.g., corticotropin-releasing factor [CRF]) and antistress (e.g., nociceptin/orphanin FQ, oxytocin) neuropeptides affect alcohol- and anxiety-related behaviors, and also alter the alcohol-induced effects on CeA neurotransmission. Alcohol dependence produces plasticity in these neuropeptide systems, reflecting a recruitment of those systems during the transition to alcohol dependence.

Sex and context differences in the effects of trauma on comorbid alcohol use and post-traumatic stress phenotypes in actively drinking rats - Kirson D,; Steinman MQ,; Wolfe SA,; Spierling Bagsic SR,; Bajo M,; Sureshchandra S,; Oleata CS,; Messaoudi I,; Zorrilla EP,; M., Roberto (J Neurosci Res, 2021)
Alcohol use disorder (AUD) and affective disorders are frequently comorbid and share underlying mechanisms that could be targets for comprehensive treatment. Post-traumatic stress disorder (PTSD) has high comorbidity with AUD, but comprehensive models of this overlap are nascent. We recently characterized a model of comorbid AUD and PTSD-like symptoms, wherein stressed rats receive an inhibitory avoidance (IA)-related footshock on two occasions followed by two-bottle choice (2BC) voluntary alcohol drinking. Stressed rats received the second footshock in a familiar (FAM, same IA box as the first footshock) or novel context (NOV, single-chambered apparatus); the FAM paradigm more effectively increased alcohol drinking in males and the NOV paradigm in females. During abstinence, stressed males displayed avoidance-like PTSD symptoms, and females showed hyperarousal-like PTSD symptoms. Rats in the model had altered spontaneous action potential-independent GABAergic transmission in the central amygdala (CeA), a brain region key in alcohol dependence and stress-related signaling. However, PTSD sufferers may have alcohol experience prior to their trauma. Here, we therefore modified our AUD/PTSD comorbidity model to provide 3 weeks of intermittent extended alcohol access before footshock and then studied the effects of NOV and FAM stress on drinking and PTSD phenotypes. NOV stress suppressed the escalation of alcohol intake and preference seen in male controls, but no stress effects were seen on drinking in females. Additionally, NOV males had decreased action potential-independent presynaptic GABA release and delayed postsynaptic GABAA receptor kinetics in the CeA compared to control and FAM males. Despite these changes to alcohol intake and CeA GABA signaling, stressed rats showed broadly similar anxiogenic-like behaviors to our previous comorbid model, suggesting decoupling of the PTSD symptoms from the AUD vulnerability for some of these animals. The collective results show the importance of alcohol history and trauma context in vulnerability to comorbid AUD/PTSD-like symptoms. Keywords: GABA; alcohol use disorder (AUD); central amygdala; post-traumatic stress disorder (PTSD); sex differences; stress; trauma.

Sex Differences in Acute Alcohol Sensitivity of Naïve and Alcohol Dependent Central Amygdala GABA Synapses - Kirson D,; Khom S,; Rodriguez L; Wolfe SA,; Varodayan FP; Gandhi PJ,; Patel RR,; Vlkolinsky R,; Bajo M,; Roberto M (Alcohol Alcohol, 2021)
Aims: Alcohol use disorder (AUD) is linked to hyperactivity of brain stress systems, leading to withdrawal states which drive relapse. AUD differs among the sexes, as men are more likely to have AUD than women, but women progress from casual use to binge and heavy alcohol use more quickly and are more likely to relapse into repetitive episodes of heavy drinking. In alcohol dependence animal models of AUD, the central amygdala (CeA) functions as a hub of stress and anxiety processing and gamma-Aminobutyric acid (GABA)ergic signaling within the CeA is involved in dependence-induced increases in alcohol consumption. We have shown dysregulation of CeA GABAergic synaptic signaling in alcohol dependence animal models, but previous studies have exclusively used males. Methods: Here, we used whole-cell patch clamp electrophysiology to examine basal CeA GABAergic spontaneous inhibitory postsynaptic currents (sIPSC) and the effects of acute alcohol in both naïve and alcohol dependent rats of both sexes. Results: We found that sIPSC kinetics differ between females and males, as well as between naïve and alcohol-dependent animals, with naïve females having the fastest current kinetics. Additionally, we find differences in baseline current kinetics across estrous cycle stages. In contrast to the increase in sIPSC frequency routinely found in males, acute alcohol (11-88 mM) had no effect on sIPSCs in naïve females, however the highest concentration of alcohol increased sIPSC frequency in dependent females. Conclusion: These results provide important insight into sex differences in CeA neuronal function and dysregulation with alcohol dependence and highlight the need for sex-specific considerations in the development of effective AUD treatment. © The Author(s) 2021. Medical Council on Alcohol and Oxford University Press. All rights reserved.

Transcriptomics identifies STAT3 as a key regulator of hippocampal gene expression and anhedonia during withdrawal from chronic alcohol exposure - Chen WY; Chen H,; Hamada K,; Gatta E; Chen Y,; Zhang H; Drnevich J,; Krishnan HR,; Maienschein-Cline M,; Grayson DR,; Pandey SC,; Lasek AW, (Translational Psychiatry, 2021)
Alcohol use disorder (AUD) is highly comorbid with depression. Withdrawal from chronic alcohol drinking results in depression and understanding brain molecular mechanisms that drive withdrawal-related depression is important for finding new drug targets to treat these comorbid conditions. Here, we performed RNA sequencing of the rat hippocampus during withdrawal from chronic alcohol drinking to discover key signaling pathways involved in alcohol withdrawal-related depressive-like behavior. Data were analyzed by weighted gene co-expression network analysis to identify several modules of co-expressed genes that could have a common underlying regulatory mechanism. One of the hub, or highly interconnected, genes in module 1 that increased during alcohol withdrawal was the transcription factor, signal transducer and activator of transcription 3 (Stat3), a known regulator of immune gene expression. Total and phosphorylated (p)STAT3 protein levels were also increased in the hippocampus during withdrawal after chronic alcohol exposure. Further, pSTAT3 binding was enriched at the module 1 genes Gfap, Tnfrsf1a, and Socs3 during alcohol withdrawal. Notably, pSTAT3 and its target genes were elevated in the postmortem hippocampus of human subjects with AUD when compared with control subjects. To determine the behavioral relevance of STAT3 activation during alcohol withdrawal, we treated rats with the STAT3 inhibitor stattic and tested for sucrose preference as a measure of anhedonia. STAT3 inhibition alleviated alcohol withdrawal-induced anhedonia. These results demonstrate activation of STAT3 signaling in the hippocampus during alcohol withdrawal in rats and in human AUD subjects, and suggest that STAT3 could be a therapeutic target for reducing comorbid AUD and depression.

Binge-Like Ethanol Drinking Activates ALK Signaling and Increases the Expression of STAT3 Target Genes in the Mouse Hippocampus and Prefrontal Cortex - Hamada K,; Ferguson LB,; Mayfield RD; Krishnan HR,; Maienschein-Cline M,; Lasek AW, (Genes Brain Behav, 2021)
Alcohol use disorder (AUD) has a complex pathogenesis, making it a difficult disorder to treat. Identifying relevant signaling pathways in the brain may be useful for finding new pharmacological targets to treat AUD. The receptor tyrosine kinase anaplastic lymphoma kinase (ALK) activates the transcription factor STAT3 in response to ethanol in cell lines. Here, we show ALK activation and upregulation of known STAT3 target genes (Socs3, Gfap and Tnfrsf1a) in the prefrontal cortex (PFC) and ventral hippocampus (HPC) of mice after 4 days of binge‐like ethanol drinking. Mice treated with the STAT3 inhibitor stattic drank less ethanol than vehicle‐treated mice, demonstrating the behavioral importance of STAT3. To identify novel ethanol‐induced target genes downstream of the ALK and STAT3 pathway, we analyzed the NIH LINCS L1000 database for gene signature overlap between ALK inhibitor (alectinib and NVP‐TAE684) and STAT3 inhibitor (niclosamide) treatments on cell lines. These genes were then compared with differentially expressed genes in the PFC of mice after binge‐like drinking. We found 95 unique gene candidates, out of which 57 had STAT3 binding motifs in their promoters. We further showed by qPCR that expression of the putative STAT3 genes Nr1h2, Smarcc1, Smarca4 and Gpnmb were increased in either the PFC or HPC after binge‐like drinking. Together, these results indicate activation of the ALK‐STAT3 signaling pathway in the brain after binge‐like ethanol consumption, identify putative novel ethanol‐responsive STAT3 target genes, and suggest that STAT3 inhibition may be a potential method to reduce binge drinking in humans.

Importance of sex and trauma context on circulating cytokines and amygdalar GABAergic signaling in a comorbid model of posttraumatic stress and alcohol use disorders - Steinman MQ,; Kirson D,; Wolfe SA,; Khom S,; D'Ambrosio SR,; Spierling Bagsic SR,; Bajo M,; Vlkolinský R,; Hoang NK,; Singhal A,; Sureshchandra S,; Oleata CS,; et al. (Molecular Psychiatry, 2021)
Alcohol use disorder (AUD) and anxiety disorders are frequently comorbid and share mechanisms that could be therapeutic targets. To facilitate mechanistic studies, we adapted an inhibitory avoidance-based “2-hit” rat model of posttraumatic stress disorder (PTSD) and identified predictors and biomarkers of comorbid alcohol (ethanol)/PTSD-like symptoms in these animals. Stressed Wistar rats received a single footshock on two occasions. The first footshock occurred when rats crossed into the dark chamber of a shuttle box. Forty-eight hours later, rats received the second footshock in a familiar (FAM) or novel (NOV) context. Rats then received 4 weeks of two-bottle choice (2BC) ethanol access. During subsequent abstinence, PTSD-like behavior responses, GABAergic synaptic transmission in the central amygdala (CeA), and circulating cytokine levels were measured. FAM and NOV stress more effectively increased 2BC drinking in males and females, respectively. Stressed male rats, especially drinking-vulnerable individuals (≥0.8 g/kg average 2-h ethanol intake with >50% ethanol preference), showed higher fear overgeneralization in novel contexts, increased GABAergic transmission in the CeA, and a profile of increased G-CSF, GM-CSF, IL-13, IL-6, IL-17a, leptin, and IL-4 that discriminated between stress context (NOV > FAM > Control). However, drinking-resilient males showed the highest G-CSF, IL-13, and leptin levels. Stressed females showed increased acoustic startle and decreased sleep maintenance, indicative of hyperarousal, with increased CeA GABAergic transmission in NOV females. This paradigm promotes key features of PTSD, including hyperarousal, fear generalization, avoidance, and sleep disturbance, with comorbid ethanol intake, in a sex-specific fashion that approximates clinical comorbidities better than existing models, and identifies increased CeA GABAergic signaling and a distinct pro-hematopoietic, proinflammatory, and pro-atopic cytokine profile that may aid in treatment.

Age-dependent impairment of metabotropic glutamate receptor 2-dependent long-term depression in the mouse striatum by chronic ethanol exposure - Johnson KA,; Liput DJ,; Homanics GE,; Lovinger DM (Alcohol, 2020)
Chronic alcohol exposure is associated with increased reliance on behavioral strategies involving the dorsolateral striatum (DLS), including habitual or stimulus-response behaviors. Presynaptic G protein-coupled receptors (GPCRs) on cortical and thalamic inputs to the DLS inhibit glutamate release, and alcohol-induced disruption of presynaptic GPCR function represents a mechanism by which alcohol could disinhibit DLS neurons and thus bias toward use of DLS-dependent behaviors. Metabotropic glutamate receptor 2 (mGlu2) is a Gi/o-coupled GPCR that robustly modulates glutamate transmission in the DLS, inducing long-term depression (LTD) at both cortical and thalamic synapses. Loss of mGlu2 function has recently been associated with increased ethanol seeking and consumption, but the ability of alcohol to produce adaptations in mGlu2 function in the DLS has not been investigated. We exposed male C57Bl/6J mice to a 2-week chronic intermittent ethanol (CIE) paradigm followed by a brief withdrawal period, then used whole-cell patch clamp recordings of glutamatergic transmission in the striatum to assess CIE effects on mGlu2-mediated synaptic plasticity. We report that CIE differentially disrupts mGlu2-mediated long-term depression in the DLS vs. dorsomedial striatum (DMS). Interestingly, CIE-induced impairment of mGlu2-LTD in the dorsolateral striatum is only observed when alcohol exposure occurs during adolescence. Incubation of striatal slices from CIE-exposed adolescent mice with a positive allosteric modulator of mGlu2 fully rescues mGlu2-LTD. In contrast to the 2-week CIE paradigm, acute exposure of striatal slices to ethanol concentrations that mimic ethanol levels during CIE exposure fails to disrupt mGlu2-LTD. We did not observe a reduction of mGlu2 mRNA or protein levels following CIE exposure, suggesting that alcohol effects on mGlu2 occur at the functional level. Our findings contribute to growing evidence that adolescents are uniquely vulnerable to certain alcohol-induced neuroadaptations, and identify enhancement of mGlu2 activity as a strategy to reverse the effects of adolescent alcohol exposure on DLS physiology.

Alcohol and IL-6 alter expression of synaptic proteins in cerebellum of transgenic mice with increased astrocyte expression of IL-6. - Gruol DL; Melkonian C,; Ly K,; Sisouvanthong J,; Tan Y,; Roberts AJ, (Neuroscience, 2020)
Recent studies indicate that neuroimmune factors, including the cytokine interleukin-6 (IL-6), play a role in the CNS actions of alcohol. The cerebellum is a sensitive target of alcohol, but few studies have examined a potential role for neuroimmune factors in the actions of alcohol on this brain region. A number of studies have shown that synaptic transmission, and in particular inhibitory synaptic transmission, is an important cerebellar target of alcohol. IL-6 also alters synaptic transmission, although it is unknown if IL-6 targets are also targets of alcohol. This is an important issue because alcohol induces glial production of IL-6, which could then covertly influence the actions of alcohol. The persistent cerebellar effects of both IL-6 and alcohol typically involve chronic exposure and, presumably, altered gene and protein expression. Thus, in the current studies we tested the possibility that proteins involved in inhibitory and excitatory synaptic transmission in the cerebellum are common targets of alcohol and IL-6. We used transgenic mice that express elevated levels of astrocyte produced IL-6 to model persistently elevated expression of IL-6, as would occur in alcohol use disorders, and a chronic intermittent alcohol exposure/withdrawal paradigm (CIE/withdrawal) that is known to produce alcohol dependence. Multiple cerebellar synaptic proteins were assessed by Western blot. Results show that IL-6 and CIE/withdrawal have both unique and common actions that affect synaptic protein expression. These common targets could provide sites for IL-6/alcohol exposure/withdrawal interactions and play an important role in cerebellar symptoms of alcohol use such as ataxia.

Alcohol dependence and withdrawal impair serotonergic regulation of GABA transmission in the rat central nucleus of the amygdala. - Khom S,; Wolfe SA,; Patel RR,; Kirson D,; Hedges DM,; Varodayan FP; Bajo M,; Roberto M (Journal of Neuroscience, 2020)
Excessive serotonin (5-HT) signaling plays a critical role in the etiology of alcohol use disorder. The central nucleus of the amygdala (CeA) is a key player in alcohol-dependence associated behaviors. The CeA receives dense innervation from the dorsal raphe nucleus, the major source of 5-HT, and expresses 5-HT receptor subtypes (e.g., 5-HT2C and 5-HT1A) critically linked to alcohol use disorder. Notably, the role of 5-HT regulating rat CeA activity in alcohol dependence is poorly investigated. Here, we examined neuroadaptations of CeA 5-HT signaling in adult, male Sprague Dawley rats using an established model of alcohol dependence (chronic intermittent alcohol vapor exposure), ex vivo slice electrophysiology and ISH. 5-HT increased frequency of sIPSCs without affecting postsynaptic measures, suggesting increased CeA GABA release in naive rats. In dependent rats, this 5-HT-induced increase of GABA release was attenuated, suggesting blunted CeA 5-HT sensitivity, which partially recovered in protracted withdrawal (2 weeks). 5-HT increased vesicular GABA release in naive and dependent rats but had split effects (increase and decrease) after protracted withdrawal indicative of neuroadaptations of presynaptic 5-HT receptors. Accordingly, 5-HT abolished spontaneous neuronal firing in naive and dependent rats but had bidirectional effects in withdrawn. Alcohol dependence and protracted withdrawal did not alter either 5-HT1A-mediated decrease of CeA GABA release or Htr1a expression but disrupted 5-HT2C-signaling without affecting Htr2c expression. Collectively, our study provides detailed insights into modulation of CeA activity by the 5-HT system and unravels the vulnerability of the CeA 5-HT system to chronic alcohol and protracted withdrawal. SIGNIFICANCE STATEMENT Elevated GABA signaling in the central nucleus of the amygdala (CeA) underlies key behaviors associated with alcohol dependence. The CeA is reciprocally connected with the dorsal raphe nucleus, the main source of serotonin (5-HT) in the mammalian brain, and excessive 5-HT signaling is critically implicated in the etiology of alcohol use disorder. Our study, using a well-established rat model of alcohol dependence, ex vivo electrophysiology and ISH, provides mechanistic insights into how both chronic alcohol exposure and protracted withdrawal dysregulate 5-HT signaling in the CeA. Thus, our study further expands our understanding of CeA cellular mechanisms involved in the pathophysiology of alcohol dependence and withdrawal.

Alcohol dependence potentiates substance P/neurokinin-1 receptor signaling in the rat central nucleus of amygdala - Khom S,; Steinkellner T,; Hnasko TS,; Roberto M (Science Advances, 2020)
Behavioral and clinical studies suggest a critical role of substance P (SP)/neurokinin-1 receptor (NK-1R) signaling in alcohol dependence. Here, we examined regulation of GABA transmission in the medial subdivision of the central amygdala (CeM) by the SP/NK-1R system, and its neuroadaptation following chronic alcohol exposure. In naïve rats, SP increased action potential–dependent GABA release, and the selective NK-1R antagonist L822429 decreased it, demonstrating SP regulation of CeM activity under basal conditions. SP induced a larger GABA release in alcohol-dependent rats accompanied by decreased NK-1R expression compared to naïve controls, suggesting NK-1R hypersensitivity which persisted during protracted alcohol withdrawal. The NK-1R antagonist blocked acute alcohol-induced GABA release in alcohol-dependent and withdrawn but not in naïve rats, indicating that dependence engages the SP/NK-1R system to mediate acute effects of alcohol. Collectively, we report long-lasting CeA NK-1R hypersensitivity corroborating that NK-1Rs are promising targets for the treatment of alcohol use disorder.

Alcohol dependence promotes systemic IFN-γ and IL-17 responses in mice - Frank K,; Abeynaike S,; Nikzad R,; Patel RR,; Roberts AJ,; Roberto M; Paust S (PLoS One, 2020)
Alcohol use disorder (AUD) is a chronic relapsing disorder characterized by an impaired ability to stop or control alcohol use despite adverse social, occupational, or health consequences. AUD is associated with a variety of physiological changes and is a substantial risk factor for numerous diseases. We aimed to characterize systemic alterations in immune responses using a well-established mouse model of chronic intermittent alcohol exposure to induce alcohol dependence. We exposed mice to chronic intermittent ethanol vapor for 4 weeks and analyzed the expression of cytokines IFN-γ, IL-4, IL-10, IL-12 and IL-17 by different immune cells in the blood, spleen and liver of alcohol dependent and non-dependent control mice through multiparametric flow cytometry. We found increases in IFN-γ and IL-17 expression in a cell type- and organ-specific manner. Often, B cells and neutrophils were primary contributors to increased IFN-γ and IL-17 levels while other cell types played a secondary role. We conclude that chronic alcohol exposure promotes systemic pro-inflammatory IFN-γ and IL-17 responses in mice. These responses are likely important in the development of alcohol-related diseases, but further characterization is necessary to understand the initiation and effects of systemic inflammatory responses to chronic alcohol exposure.

Alcohol Enhances Responses to High Frequency Stimulation in Hippocampus from Transgenic Mice with Increased Astrocyte Expression of IL-6. - Gruol DL; Hernandez RV,; Roberts A (Cellular and Molecular Neurobiology, 2020)
Recent studies show that alcohol exposure can induce glial production of neuroimmune factors in the CNS. Of these, IL-6 has gained attention because it is involved in a number of important physiological and pathophysiological processes that could be affected by alcohol-induced CNS production of IL-6, particularly under conditions of excessive alcohol use. For example, IL-6 has been shown to play a role in hippocampal behaviors and synaptic plasticity (long-term potentiation; LTP) associated with memory and learning. Surprisingly, in our in vitro studies of LTP at the Schaffer collateral to CA1 pyramidal neuron synapse in hippocampus from transgenic mice that express elevated levels of astrocyte produced IL-6 (TG), LTP was not altered by the increased levels of IL-6. However, exposure to acute alcohol revealed neuroadaptive changes that served to protect LTP against the alcohol-induced reduction of LTP observed in hippocampus from non-transgenic control mice (WT). Here we examined the induction phase of LTP to assess if presynaptic neuroadaptive changes occurred in the hippocampus of TG mice that contributed to the resistance of LTP to alcohol. Results are consistent with a role for IL-6-induced neuroadaptive effects on presynaptic mechanisms involved in transmitter release in the resistance of LTP to alcohol in hippocampus from the TG mice. These actions are important with respect to a role for IL-6 in physiological and pathophysiological processes in the CNS and in CNS actions of alcohol, especially when excessive alcohol used is comorbid with conditions associated with elevated levels of IL-6 in the CNS.

Ampicillin/sulbactam treatment modulates NMDA receptor NR2B subunit and attenuates neuroinflammation and alcohol intake in male high alcohol drinking rats. - Alasmari F,; Alhaddad H,; Wong W,; Bell RL,; Sari Y, (Biomolecules, 2020)
Exposure to ethanol commonly manifests neuroinflammation. Beta (β)-lactam antibiotics attenuate ethanol drinking through upregulation of astroglial glutamate transporters, especially glutamate transporter-1 (GLT-1), in the mesocorticolimbic brain regions, including the nucleus accumbens (Acb). However, the effect of β-lactam antibiotics on neuroinflammation in animals chronically exposed to ethanol has not been fully investigated. In this study, we evaluated the effects of ampicillin/sulbactam (AMP/SUL, 100 and 200 mg/kg, i.p.) on ethanol consumption in high alcohol drinking (HAD1) rats. Additionally, we investigated the effects of AMP/SUL on GLT-1 and N-methyl-d-aspartate (NMDA) receptor subtypes (NR2A and NR2B) in the Acb core (AcbCo) and Acb shell (AcbSh). We found that AMP/SUL at both doses attenuated ethanol consumption and restored ethanol-decreased GLT-1 and NR2B expression in the AcbSh and AcbCo, respectively. Moreover, AMP/SUL (200 mg/kg, i.p.) reduced ethanol-increased high mobility group box 1 (HMGB1) and receptor for advanced glycation end-products (RAGE) expression in the AcbSh. Moreover, both doses of AMP/SUL attenuated ethanol-elevated tumor necrosis factor-alpha (TNF-α) in the AcbSh. Our results suggest that AMP/SUL attenuates ethanol drinking and modulates NMDA receptor NR2B subunits and HMGB1-associated pathways. Keywords: ethanol, AMP/SUL, GLT-1, NMDA, neuroinflammation

Anaplastic Lymphoma Kinase Regulates Internalization of the Dopamine D2 Receptor - He D,; Lasek AW, (Molecular Pharmacology, 2020)
The dopamine D2 receptor (D2R) is a G protein-coupled receptor (GPCR) expressed in regions of the brain that control motor function, cognition, and motivation. As a result, D2R is involved in the pathophysiology of disorders such as schizophrenia and drug addiction. Understanding the signaling pathways activated by D2R is crucial to finding new therapeutic targets for these disorders. D2R stimulation by its agonist, dopamine, causes desensitization and internalization of the receptor. A previous study found that inhibitors of the receptor tyrosine kinase anaplastic lymphoma kinase (ALK) blocked D2R desensitization in neurons in the ventral tegmental area of the brain. In the present study, using a cell-based system, we investigated whether ALK regulates D2R internalization. The ALK inhibitor alectinib completely inhibited dopamine-induced D2R internalization. Since GPCRs can transactivate receptor tyrosine kinases, we also examined if D2R stimulation activated ALK signaling. ALK phosphorylation increased by almost 2-fold after dopamine treatment and ALK coimmunoprecipitated with D2R. To identify the signaling pathways downstream of ALK that might regulate D2R internalization, we used pharmacological inhibitors of proteins activated by ALK signaling. Protein kinase Cγ was activated by dopamine in an ALK-dependent manner, and a protein kinase C inhibitor completely blocked dopamine-induced D2R internalization. Taken together, these results identify ALK as a receptor tyrosine kinase transactivated by D2R that promotes its internalization, possibly through activation of protein kinase C. ALK inhibitors could be useful in enhancing D2R signaling. SIGNIFICANCE STATEMENT Receptor internalization is a mechanism by which receptors are desensitized. In this study we found that agonist-induced internalization of the dopamine D2 receptor is regulated by the receptor tyrosine kinase ALK. ALK was also transactivated by and associated with dopamine D2 receptor. Dopamine activated protein kinase C in an ALK-dependent manner and a PKC inhibitor blocked dopamine D2 receptor internalization. These results indicate that ALK regulates dopamine D2 receptor trafficking, which has implications for psychiatric disorders involving dysregulated dopamine signaling.

Apremilast regulates acute effects of ethanol and other GABAergic drugs via protein kinase A-dependent signaling. - Blednov YA,; Borghese CM,; Dugan MP,; Pradhan S,; Thodati TM,; Kichili NR,; Harris RA; Messing RO, (Neuropharmacology, 2020)
Phosphodiesterase type 4 (PDE4) inhibitors prevent hydrolysis of cyclic adenosine monophosphate and increase protein kinase A (PKA)-mediated phosphorylation. PDE4 inhibitors also regulate responses to ethanol and GABAergic drugs. We investigated mechanisms by which the PDE4 inhibitor, apremilast, regulates acute effects of ethanol and GABAergic drugs in male and female mice. Apremilast prolonged the sedative-hypnotic effects of gaboxadol, zolpidem, and propofol but did not alter etomidate effects, and unexpectedly shortened the sedative-hypnotic effects of diazepam. Apremilast prolonged rotarod ataxia induced by zolpidem, propofol, and loreclezole, shortened recovery from diazepam, but had no effect on ataxia induced by gaboxadol or etomidate. The PKA inhibitor H-89 blocked apremilast's ability to prolong the sedative-hypnotic effects of ethanol, gaboxadol, and propofol and to prolong ethanol- and propofol-induced ataxia. H-89 also blocked apremilast's ability to shorten the sedative-hypnotic and ataxic effects of diazepam. The β1-specific antagonist, salicylidene salicylhydrazide (SCS), produced faster recovery from ethanol- and diazepam-induced ataxia, but did not alter propofol- or etomidate-induced ataxia. SCS shortened the sedative-hypnotic effects of ethanol and diazepam but not of propofol. In Xenopus oocytes, a phosphomimetic (aspartate) mutation at the PKA phosphorylation site in β1 subunits decreased the maximal GABA current in receptors containing α1 or α3, but not α2 subunits. In contrast, phosphomimetic mutations at PKA sites in β3 subunits increased the maximal GABA current in receptors containing α1 or α2, but not α3 subunits. The GABA potency and allosteric modulation by ethanol, propofol, etomidate, zolpidem, flunitrazepam, or diazepam were not altered by these mutations. We propose a model whereby apremilast increases PKA-mediated phosphorylation of β1-and β3-containing GABAA receptors and selectively alters acute tolerance to ethanol and GABAergic drugs.

Atrial natriuretic peptide (ANP): A novel mechanism for reducing ethanol consumption and seeking behaviors in female alcohol preferring (P) rats. - Hauser SR,; Waeiss RA,; Molosh AI,; Deehan GA Jr,; Bell RL,; McBride WJ,; Rodd ZA (Peptides, 2020)
Atrial Naturietic Peptide (ANP) is a neuropeptide that regulates function of the hypothalamic-pituitary-adrenal (HPA) axis, immune and neuroimmune system, and epigenetic factors. Research has indicated that ANP may mediate alcohol intake, withdrawal, and craving like behaviors. ANP receptors are present in the mesocorticolimbic (MCL) reward pathway of the brain, which includes the nucleus accumbens (Acb) and the ventral tegmental area (VTA). The objectives of the present study were to examine the effects of ANP microinjected into Acb subregions (Shell (Sh), Core (Co), ventral to AcbSh) on operant ethanol (EtOH) self-administration and into posterior VTA (pVTA) on EtOH-seeking behavior of female alcohol-preferring (P) rats. In the first experiment, ANP (0, 10 μg, or 100 μg) was microinjected into subregions of the Acb to determine its effects on EtOH self-administration. In the second experiment, ANP was microinjected into pVTA to determine its effects on Pavlovian Spontaneous Recovery (PSR) of responding, a measure of context-induced EtOH-seeking behavior. Administration of ANP directly into the AcbSh significantly reduced EtOH self-administration compared to vehicle, whereas ANP into the AcbCo or areas directly ventral to the AcbSh did not alter responding for EtOH. Microinjection of ANP into the pVTA significantly reduced responding on the EtOH-associated lever during the PSR test. The data indicate that activation of ANP systems in the (a) AcbSh can inhibit EtOH intake, and (b) in the pVTA can inhibit EtOH-seeking behavior. The results suggest that manipulations of the ANP system could be a potential target for pharmacotherapeutic intervention to treat alcohol use disorder. Supported in part by AA07462, AA07611, AA10717, AA10721, AA013522, AA019366, AA020908, AA022287, and AA024612. Keywords: Alcohol; Alcohol preferring P rats; Atrial natriuretic peptide; Nucleus accumbens; Ventral tegmental Area.

Cessation of fluoxetine treatment increases alcohol seeking during relapse and dysregulates endocannabinoid and glutamatergic signaling in the central amygdala. - Suárez, J; Khom, S; Alén, F; Natividad, LA; Varodayan, FP; Patel, RR; Kirson, D; Arco, R; Ballesta, A; Bajo, M; Rubio, L; Martin-Fardon, R (Addict Biology, 2020)
Administration of selective serotonin reuptake inhibitors (SSRIs), typically used as antidepressants, induces long-lasting behavioral changes associated with alcohol use disorder (AUD). However, the contribution of SSRI (fluoxetine)-induced alterations in neurobiological processes underlying alcohol relapse such as endocannabinoid and glutamate signaling in the central amygdala (CeA) remains largely unknown. We utilized an integrative approach to study the effects of repeated fluoxetine administration during abstinence on ethanol drinking. Gene expression and biochemical and electrophysiological studies explored the hypothesis that dysregulation in glutamatergic and endocannabinoid mechanisms in the CeA underlie the susceptibility to alcohol relapse. Cessation of daily treatment with fluoxetine (10 mg/kg) during abstinence resulted in a marked increase in ethanol seeking during re-exposure periods. The increase in ethanol self-administration was associated with (a) reductions in levels of the endocannabinoids N-arachidonoylethanolomine and 2-arachidonoylglycerol in the CeA, (b) increased amygdalar gene expression of cannabinoid type-1 receptor (CB1), N-acyl phosphatidylethanolamine phospholipase D (Nape-pld), fatty acid amid hydrolase (Faah), (c) decreased amygdalar gene expression of ionotropic AMPA (GluA2 and GluA4) and metabotropic (mGlu3) glutamate receptors, and (d) increased glutamatergic receptor function. Overall, our data suggest that the administration of the antidepressant fluoxetine during abstinence dysregulates endocannabinoid signaling and glutamatergic receptor function in the amygdala, facts that likely facilitate alcohol drinking behavior during relapse.

Chronic Chemogenetic Stimulation of the Nucleus Accumbens Produces Lasting Reductions in Binge Drinking and Ameliorates Alcohol-Related Morphological and Transcriptional Changes - Pozhidayeva DY,; Farris SP,; Goeke CM,; Firsick EJ,; Townsley KG,; Guizzetti M,; Ozburn AR, (Brain Sciences, 2020)
Binge drinking is a dangerous pattern of behavior. We tested whether chronically manipulating nucleus accumbens (NAc) activity (via clozapine-N-oxide (CNO) and Designer Receptors Exclusively Activated by Designer Drugs (DREADD)) could produce lasting effects on ethanol binge-like drinking in mice selectively bred to drink to intoxication. We found chronically increasing NAc activity (4 weeks, via CNO and the excitatory DREADD, hM3Dq) decreased binge-like drinking, but did not observe CNO-induced changes in drinking with the inhibitory DREADD, hM4Di. The CNO/hM3Dq-induced reduction in ethanol drinking persisted for at least one week, suggesting adaptive neuroplasticity via transcriptional and epigenetic mechanisms. Therefore, we defined this plasticity at the morphological and transcriptomic levels. We found that chronic binge drinking (6 weeks) altered neuronal morphology in the NAc, an effect that was ameliorated with CNO/hM3Dq. Moreover, we detected significant changes in expression of several plasticity-related genes with binge drinking that were ameliorated with CNO treatment (e.g., Hdac4). Lastly, we found that LMK235, an HDAC4/5 inhibitor, reduced binge-like drinking. Thus, we were able to target specific molecular pathways using pharmacology to mimic the behavioral effects of DREADDs.

Chronic Ethanol Consumption Alters Glucocorticoid Receptor Isoform Expression in Stress Neurocircuits and Mesocorticolimbic Brain Regions of Alcohol-Preferring Rats - Alhaddad H,; Gordon DM,; Bell RL,; Jarvis EE,; Kipp ZA,; Hinds TD Jr,; Sari Y, (Neuroscience, 2020)
Evidence suggests the hypothalamic–pituitary–adrenal (HPA) axis is involved in Alcohol Use Disorders (AUDs), which might be mediated by an imbalance of glucocorticoid receptor (GR), GRα and GRβ, activity. GRβ antagonizes the GRα isoform to cause glucocorticoid (GC) resistance. In the present study, we aimed to investigate the effects of chronic continuous free-choice access to ethanol on GR isoform expression in subregions of the mesocorticolimbic reward circuit. Adult male alcohol-preferring (P) rats had concurrent access to 15% and 30% ethanol solutions, with ad lib access to lab chow and water, for six weeks. Quantitative Real-time PCR (RT-PCR) analysis showed that chronic ethanol consumption reduced GRα expression in the nucleus accumbens shell (NAcsh) and hippocampus, whereas ethanol drinking reduced GRβ in the nucleus accumbens core (NAcc), prefrontal cortex (PFC), and hippocampus. An inhibitor of GRα, microRNA-124-3p (miR124-3p) was significantly higher in the NAcsh, and GC-induced gene, GILZ, as a measure of GC-responsiveness, was significantly lower. These were not changed in the NAcc. Likewise, genes associated with HPA axis activity were not significantly changed by ethanol drinking [i.e., corticotrophin-releasing hormone (Crh), adrenocorticotrophic hormone (Acth), and proopiomelanocortin (Pomc)] in these brain regions. Serum corticosterone levels were not changed by ethanol drinking. These data indicate that the expression of GRα and GRβ isoforms are differentially affected by ethanol drinking despite HPA-associated peptides remaining unchanged, at least at the time of tissue harvesting. Moreover, the results suggest that GR changes may stem from ethanol-induced GC-resistance in the NAcsh. These findings confirm a role for stress in high ethanol drinking, with GRα and GRβ implicated as targets for the treatment of AUDs.

Chronic Voluntary Ethanol Drinking in Cynomolgus Macaques Elicits Gene Expression Changes in Prefrontal Cortical Area 46 - Walter NAR,; Zheng CL,; Searles RP,; McWeeney SK,; Grant KA,; Hitzemann R, (Alcoholism: Clinical and Experimental Research, 2020)
Background Genome‐wide profiling to examine brain transcriptional features associated with excessive ethanol (EtOH) consumption has been applied to a variety of species including rodents, nonhuman primates (NHPs), and humans. However, these data were obtained from cross‐sectional samples which are particularly vulnerable to individual variation when obtained from small outbred populations typical of human and NHP studies. In the current study, a novel within‐subject design was used to examine the effects of voluntary EtOH consumption on prefrontal cortex (PFC) gene expression in a NHP model. Methods Two cohorts of cynomolgus macaques (n = 23) underwent a schedule‐induced polydipsia procedure to establish EtOH self‐administration followed by 6 months of daily open access to EtOH (4% w/v) and water. Individual daily EtOH intakes ranged from an average of 0.7 to 3.7 g/kg/d. Dorsal lateral PFC area 46 (A46) brain biopsies were collected in EtOH‐naïve and control monkeys; contralateral A46 biopsies were collected from the same monkeys following the 6 months of fluid consumption. Gene expression changes were assessed using RNA‐Seq paired analysis, which allowed for correction of individual baseline differences in gene expression. Results A total of 675 genes were significantly down‐regulated following EtOH consumption; these were functionally enriched for immune response, cell adhesion, plasma membrane, and extracellular matrix. A total of 567 genes that were up‐regulated following EtOH consumption were enriched in microRNA target sites and included target sites associated with Toll‐like receptor pathways. The differentially expressed genes were also significantly enriched in transcription factor binding sites. Conclusions The data presented here are the first to use a longitudinal biopsy strategy to examine how chronic EtOH consumption affects gene expression in the primate PFC. Prominent effects were seen in both cell adhesion and neuroimmune pathways; the latter contained both pro‐ and antiinflammatory genes. The data also indicate that changes in miRNAs and transcription factors may be important epigenetic regulators of EtOH consumption.

Chronic voluntary ethanol drinking in cynomolgus macaques elicits gene expression changes in prefrontal cortical area 46. - Walter NAR,; Zheng CL,; Searles RP,; McWeeney SK,; Grant KA,; Hitzemann RJ, (Alcoholism: Clinical and Experimental Research, 2020)
Background: Genome-wide profiling to examine brain transcriptional features associated with excessive ethanol (EtOH) consumption has been applied to a variety of species including rodents, nonhuman primates (NHPs), and humans. However, these data were obtained from cross-sectional samples which are particularly vulnerable to individual variation when obtained from small outbred populations typical of human and NHP studies. In the current study, a novel within-subject design was used to examine the effects of voluntary EtOH consumption on prefrontal cortex (PFC) gene expression in a NHP model. Methods: Two cohorts of cynomolgus macaques (n = 23) underwent a schedule-induced polydipsia procedure to establish EtOH self-administration followed by 6 months of daily open access to EtOH (4% w/v) and water. Individual daily EtOH intakes ranged from an average of 0.7 to 3.7 g/kg/d. Dorsal lateral PFC area 46 (A46) brain biopsies were collected in EtOH-naïve and control monkeys; contralateral A46 biopsies were collected from the same monkeys following the 6 months of fluid consumption. Gene expression changes were assessed using RNA-Seq paired analysis, which allowed for correction of individual baseline differences in gene expression. Results: A total of 675 genes were significantly down-regulated following EtOH consumption; these were functionally enriched for immune response, cell adhesion, plasma membrane, and extracellular matrix. A total of 567 genes that were up-regulated following EtOH consumption were enriched in microRNA target sites and included target sites associated with Toll-like receptor pathways. The differentially expressed genes were also significantly enriched in transcription factor binding sites. Conclusions: The data presented here are the first to use a longitudinal biopsy strategy to examine how chronic EtOH consumption affects gene expression in the primate PFC. Prominent effects were seen in both cell adhesion and neuroimmune pathways; the latter contained both pro- and antiinflammatory genes. The data also indicate that changes in miRNAs and transcription factors may be important epigenetic regulators of EtOH consumption. Keywords: Brain Gene Expression; Cortex; Cynomolgus Macaque; EtOH.

Coincubation of sperm with epididymal extracellular vesicle preparations from chronic intermittent ethanol-treated mice is sufficient to impart anxiety-like and ethanol-induced behaviors to adult progeny. - Rompala GR; Ferguson C,; Homanics GE, (Alcohol, 2020)
We previously reported that paternal preconception chronic ethanol exposure in mice imparts adult male offspring with reduced ethanol drinking preference and consumption, increased ethanol sensitivity, and attenuated stress responsivity. That same chronic ethanol exposure paradigm was later revealed to affect the sperm epigenome by altering the abundance of several small noncoding RNAs, a mechanism that mediates the intergenerational effects of numerous paternal environmental exposures. Although recent studies have revealed that the unique RNA signature of sperm is shaped during maturation in the epididymis via extracellular vesicles (EVs), formal demonstration that EVs mediate the effects of paternal preconception perturbations is lacking. Therefore, in the current study we tested the hypothesis that epididymal EV preparations are sufficient to induce intergenerational effects of paternal preconception ethanol exposure on offspring. To test this hypothesis, sperm from ethanol-naïve donors were incubated with epididymal EV preparations from chronic ethanol (Ethanol EV-donor) or control-treated (Control EV-donor) mice prior to in vitro fertilization (IVF) and embryo transfer. Progeny were examined for ethanol- and stress-related behaviors in adulthood. Ethanol EV-donors imparted reduced body weight at weaning and imparted modestly increased limited access ethanol intake to male offspring. Ethanol-EV donors also imparted increased basal anxiety-like behavior and reduced sensitivity to ethanol-induced anxiolysis to female offspring. Although Ethanol EV-donor treatment did not recapitulate the ethanol- or stress-related intergenerational effects of paternal ethanol following natural mating, these results demonstrate that coincubation of sperm with epididymal EV preparations is sufficient to impart intergenerational effects of ethanol through the male germline. This mechanism may generalize to the intergenerational effects of a wide variety of paternal preconception perturbations.

Corticotropin releasing factor, but not alcohol, modulates norepinephrine release in the rat central nucleus of the amygdala. - Hedges DM,; Yorgason JT,; Brundage JN,; Wadsworth HA,; Williams B,; Steffensen SC,; Roberto M (Neuropharmacology, 2020)
Alcohol misuse and dependence is a widespread health problem. The central nucleus of the amygdala (CeA) plays important roles in both the anxiety associated with alcohol (ethanol) dependence and the increased alcohol intake that is observed during withdrawal in dependent animals. We and others have shown the essential involvement of the corticotropin releasing factor (CRF) system in alcohol's synaptic effects on the CeA and in the development of ethanol dependence. Another system that has been shown to be critically involved in the molecular underpinnings of alcohol dependence is the norepinephrine (NE) system originating in the locus coeruleus. Both the CRF and NE systems act in concert to facilitate a stress response: central amygdalar afferents release CRF in the locus coeruleus promoting widespread release of NE. In this study, we are the first to use fast-scan cyclic voltammetry to classify local electrically-evoked NE release in the CeA and to determine if acute alcohol and CRF modulate it. Evoked NE release is action potential dependent, is abolished after depletion of monoaminergic vesicles, differs pharmacologically from dopamine release, is insensitive to acute alcohol, and decreases in response to locally applied CRF. Taken together, these results indicate that NE release in the CeA is released canonically in a vesicular-dependent manner, and that while acute alcohol does not directly alter NE release, CRF decreases it. Our results suggest that CRF acts locally on NE terminals as negative feedback and potentially prevents hyperactivation of the CRF-norepinephrine stress pathway.

. The COVID-19 Drug and Gene Set Library. - Kuleshov MV,; Stein DJ,; Clarke DJB,; Kropiwnicki E,; Jagodnik KM,; Bartal A,; Evangelista JE,; Hom J,; Cheng M,; Bailey A,; Zhou A,; Ferguson LB,; et al. (Patterns, 2020)
In a short period, many research publications that report sets of experimentally validated drugs as potential COVID-19 therapies have emerged. To organize this accumulating knowledge, we developed the COVID-19 Drug and Gene Set Library (https://amp.pharm.mssm.edu/covid19/), a collection of drug and gene sets related to COVID-19 research from multiple sources. The platform enables users to view, download, analyze, visualize, and contribute drug and gene sets related to COVID-19 research. To evaluate the content of the library, we compared the results from six in vitro drug screens for COVID-19 repurposing candidates. Surprisingly, we observe low overlap across screens while highlighting overlapping candidates that should receive more attention as potential therapeutics for COVID-19. Overall, the COVID-19 Drug and Gene Set Library can be used to identify community consensus, make researchers and clinicians aware of new potential therapies, enable machine-learning applications, and facilitate the research community to work together toward a cure.

CRISPR Turbo Accelerated KnockOut (CRISPy TAKO) for Rapid in vivo Screening of Gene Function. - Plasi SL,; Seth A,; Homanics GE, (Frontiers in Genome Editing, 2020)
The development of CRISPR/Cas9 technology has vastly sped up the process of genome editing by introducing a bacterial system that can be exploited for reverse genetics-based research. However, generating homozygous knockout (KO) animals using traditional CRISPR/Cas9-mediated techniques requires three generations of animals. A founder animal with a desired mutation is crossed to produce heterozygous F1 offspring which are subsequently interbred to generate homozygous F2 KO animals. This study describes a novel adaptation of the CRISPR/Cas9-mediated method to develop a homozygous gene-targeted KO animal cohort in one generation. A well-characterized ethanol-responsive gene, MyD88, was chosen as a candidate gene for generation of MyD88-/- mice as proof of concept. Previous studies have reported changes in ethanol-related behavioral outcomes in MyD88 KO mice. Therefore, it was hypothesized that a successful one-generation KO of MyD88 should reproduce decreased responses to ethanols sedative effects, as well as increased ethanol consumption in males that were observed in previous studies. One-cell mouse embryos were simultaneously electroporated with four gRNAs targeting a critical Exon of MyD88 along with Cas9. DNA and RNA analysis of founder mice revealed a complex mix of genetic alterations, all of which were predicted to ablate MyD88 gene function. This study additionally compared responses of Mock treatment control mice generated through electroporation to controls purchased from a vendor. No substantial behavioral changes were noted between control cohorts. Overall, the CRISPR/Cas9 KO protocol reported here, which we call CRISPR Turbo Accelerated KnockOut (CRISPy TAKO), will be useful for reverse genetic in vivo screens of gene function in whole animals.

Effects of chemogenetic manipulation of the nucleus accumbens core in male C57BL/6J mice. - Townsley KG,; Borrego MB,; Ozburn AR, (Alcohol, 2020)
Binge drinking is a widespread public health concern with limited effective treatment options. To better select pharmaceutical targets, it is imperative to expand our knowledge of the underlying neural mechanisms involved in binge drinking. Our previous experiments in C57BL/6J female mice found that increasing activity in the nucleus accumbens (NAc) core using excitatory Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) reduced binge-like drinking. These results differed from what has been found in males; however, it is unclear whether differences in experimental procedures or sex underlie these discrepancies. We matched the conditions used in our female study and asked whether bidirectional manipulation of NAc core activity has different effects on binge-like drinking in males. Male C57BL/6J mice were stereotaxically injected with AAV2 hSyn-HA hM3Dq (excitatory), -hM4Di (inhibitory), or -eGFP bilaterally into the NAc core. We tested the effects of altering NAc activity on binge-like ethanol intake using Drinking in the Dark (DID). During the first week, mice were pre-treated with vehicle to establish baseline ethanol intake. In week 2, mice were treated with 1 mg/kg CNO prior to DID to determine the effects of DREADD-induced changes in NAc core activity on ethanol intake. Decreasing activity via CNO/hM4Di significantly decreased binge-like drinking in male mice relative to eGFP and hM4Di groups. We also measured intake of sucrose, quinine, and water after CNO treatment and found that increasing NAc core activity via CNO/hM3Dq increased quinine intake, and increased water intake over time. We did not observe significant differences in the GFP or hM4Di groups. This work suggests there exist apparent sex-related differences in NAc core contributions to binge-like alcohol drinking, thus demonstrating the need for inclusion of both sexes in future work.

Effects of chronic ethanol consumption on the expression of GLT-1 and neuroplasticity-related proteins in the nucleus accumbens of alcohol-preferring rats. - Alhaddad H,; Alasmari F,; Alhamadani B,; Wong W,; Bell RL,; Sari Y. (Brain Research Bulletin, 2020)
Chronic ethanol exposure induces impairments in CNS excitatory and inhibitory activity. These impairments are associated with glutamatergic dysfunction, including altered neuroplasticity. This study examined the effects of 6-week ethanol (15% and 30% v/v) consumption, by male alcohol-preferring P rats, on protein expression associated with neuroplasticity and glutamate transporter-1 (GLT-1) function. The latter regulates intra- and extra-synaptic glutamate levels. We focused on the shell and core subregions of the nucleus accumbens (Acb); i.e., shell (AcbSh) and core (AcbCo), for these measures. Chronic ethanol exposure increased the expression of BDNF, Arc and phosphorylated (p)-post-synaptic density protein-95 (p-PSD-95) in the AcbSh of P rats. Moreover, the ratio of phospho-neuronal nitric oxide synthase (p-nNOS) to total nNOS was also increased in the AcbSh. These changes in BDNF, Arc and p-nNOS/nNOS ratio were not observed in the AcbCo. Furthermore, chronic ethanol consumption reduced GLT-1 expression in the AcbSh. Alternatively, treatment with ceftriaxone (CEF), a known GLT-1 upregulator, abolished the effect of chronic ethanol consumption on BDNF expression in the AcbSh. Overall, the present findings confirm that chronic ethanol consumption modulates activity-associated synaptic proteins, including BDNF, Arc and nNOS in a subregion-specific (i.e., in the AcbSh but not AcbCo) manner. Thus, alterations in mesocorticolimbic glutamatergic homeostasis and neuroplasticity are possible functional targets for the treatment of alcohol use disorders. Keywords: Arc; BDNF; Ethanol dependence; GLT-1; glutamate; nNOS; nucleus accumbens.

Effects of Pharmacologically Targeting Neuroimmune Pathways on Alcohol Drinking in Mice Selectively Bred to Drink to Intoxication - Ozburn AR,; Metten P,; Potretzke S,; Townsley KG,; Blednov YA,; Crabbe JC, (Alcoholism: Clinical and Experimental Research, 2020)
Abstract Background Rodent models of high alcohol drinking offer opportunities to better understand factors for alcohol use disorders (AUD) and test potential treatments. Selective breeding was carried out to create 2 unique High Drinking in the Dark (HDID‐1, HDID‐2) mouse lines that represent models of genetic risk for binge‐like drinking. A number of studies have indicated that neuroimmune genes are important for regulation of alcohol drinking. We tested whether compounds shown to reduce drinking in other models also reduce alcohol intake in these unique genetic lines. Methods We report tests of gabapentin, tesaglitazar, fenofibrate, caffeic acid phenethyl ester (CAPE), ibrutinib, and rolipram. Although these compounds have different mechanisms of action, they have all been shown to reduce inflammatory responses. We evaluated effects of these compounds on alcohol intake. In order to facilitate comparison with previously published findings for some compounds, we employed similar schedules that were previously used for that compound. Results Gabapentin increased ethanol (EtOH) binge‐like alcohol drinking in female HDID‐1 and HS/NPT mice. Tesaglitazar and fenofibrate did not alter 2‐bottle choice (2BC) drinking in male HDID‐1 or HS/NPT mice. However, tesaglitazar had no effect on DID EtOH intake but reduced blood alcohol levels (BAL), and fenofibrate increased DID intake with no effects on BAL. CAPE had no effect on EtOH intake. Ibrutinib reduced intake in female HDID‐1 in initial testing, but did not reduce intake in a second week of testing. Rolipram reduced DID intake and BALs in male and female HDID‐1, HDID‐2, and HS/NPT mice. Conclusions A number of compounds shown to reduce EtOH drinking in other models, and genotypes are not effective in HDID mice or their genetically heterogeneous founders, HS/NPT. The most promising compound was the PDE4 inhibitor, rolipram. These results highlight the importance of assessing generalizability when rigorously testing compounds for therapeutic development.

Effects of tacrolimus and other immune targeting compounds on binge-like ethanol drinking in high drinking in the dark mice - Grigsby KB,; Savarese AM,; Metten P,; Mason BJ,; Blednov YA,; Crabbe JC,; Ozburn AR, (Neurosci Insights, 2020)
High Drinking in the Dark (HDID-1) mice represent a unique genetic risk model of binge-like drinking and a novel means of screening potential pharmacotherapies to treat alcohol use disorders (AUDs). We tested the effects of tacrolimus (0, 0.5, 1, and 2 mg/kg), sirolimus (0, 5, 10, and 20 mg/kg), palmitoylethanolamide (PEA; 0, 75, 150, and 225 mg/kg), and secukinumab (0, 5, 20, and 60 mg/kg) on binge-like ethanol intake (2-day, "Drinking in the Dark" [DID]) and blood alcohol levels (BALs) in HDID-1 mice. Tacrolimus reduced ethanol intake and BALs. Tacrolimus had no effect on water intake, but reduced saccharin intake. There was no effect of sirolimus, PEA, or secukinumab on ethanol intake or BALs. These results compare and contrast with previous work addressing these compounds or their targeted mechanisms of action on ethanol drinking, highlighting the importance of screening a wide range of models and genotypes to inform the role of neuroimmune signaling in AUDs.

Epigenetic changes on rat chromosome 4 contribute to disparate alcohol drinking behavior in alcohol-preferring and -nonpreferring rats. - Spence JP,; Lai D,; Reiter JL,; Cao S,; Bell RL,; Williams KE,; Liang T, (Alcohol, 2020)
After decades of uncertainties and drawbacks, the study on the role and significance of acetaldehyde in the effects of ethanol seemed to have found its main paths. Accordingly, the effects of acetaldehyde, after its systemic or central administration and as obtained following ethanol metabolism, looked as they were extensively characterized. However, almost 5 years after this research appeared at its highest momentum, the investigations on this topic have been revitalized on at least three main directions: (1) the role and the behavioral significance of acetaldehyde in different phases of ethanol self-administration and in voluntary ethanol consumption; (2) the distinction, in the central effects of ethanol, between those arising from its non-metabolized fraction and those attributable to ethanol-derived acetaldehyde; and (3) the role of the acetaldehyde-dopamine condensation product, salsolinol. The present review article aims at presenting and discussing prospectively the most recent data accumulated following these three research pathways on this never-ending story in order to offer the most up-to-date synoptic critical view on such still unresolved and exciting topic. Keywords: ethanol, acetaldehyde, salsolinol, ethanol metabolism, epigenetics, neuroinflammation, mesolimbic system, dopamine

Estrogen receptor α regulates ethanol excitation of ventral tegmental area neurons and binge drinking in female mice. - Vandegrift BJ,; Hilderbrand ER,; Satta R,; Tai R,; He D,; You C,; Chen H,; Xu P,; Coles C,; Brodie MS,; Lasek AW, (Journal of Neuroscience, 2020)
Elevations in estrogen (17β-estradiol, E2) are associated with increased alcohol drinking by women and experimentally in rodents. E2 alters the activity of the dopamine system, including the VTA and its projection targets, which plays an important role in binge drinking. A previous study demonstrated that, during high E2 states, VTA neurons in female mice are more sensitive to ethanol excitation. However, the mechanisms responsible for the ability of E2 to enhance ethanol sensitivity of VTA neurons have not been investigated. In this study, we used selective agonists and antagonists to examine the role of ER subtypes (ERα and ERβ) in regulating the ethanol sensitivity of VTA neurons in female mice and found that ERα promotes the enhanced ethanol response of VTA neurons. We also demonstrated that enhancement of ethanol excitation requires the activity of the metabotropic glutamate receptor, mGluR1, which is known to couple with ERα at the plasma membrane. To investigate the behavioral relevance of these findings, we administered lentivirus-expressing short hairpin RNAs targeting either ERα or ERβ into the VTA and found that knockdown of each receptor in the VTA reduced binge-like ethanol drinking in female, but not male, mice. Reducing ERα in the VTA had a more dramatic effect on binge-like drinking than reducing ERβ, consistent with the ability of ERα to alter ethanol sensitivity of VTA neurons. These results provide important insight into sex-specific mechanisms that drive excessive alcohol drinking.

Genome-wide association studies of the self-rating of effects of ethanol (SRE) - Lai D,; Wetherill L,; Kapoor M,; Johnson EC,; Schwandt M,; Ramchandani VA,; Goldman D,; Joslyn G,; Rao X,; Liu Y,; Farris S; Mayfield RD; et al. (Addiction Biology, 2020)
The level of response (LR) to alcohol as measured with the Self-Report of the Effects of Alcohol Retrospective Questionnaire (SRE) evaluates the number of standard drinks usually required for up to four effects. The need for a higher number of drinks for effects is genetically influenced and predicts higher risks for heavy drinking and alcohol problems. We conducted genome-wide association study (GWAS) in the African-American (COGA-AA, N = 1527 from 309 families) and European-American (COGA-EA, N = 4723 from 956 families) subsamples of the Collaborative Studies on the Genetics of Alcoholism (COGA) for two SRE scores: SRE-T (average of first five times of drinking, the period of heaviest drinking, and the most recent 3 months of consumption) and SRE-5 (the first five times of drinking). We then meta-analyzed the two COGA subsamples (COGA-AA + EA). Both SRE-T and SRE-5 were modestly heritable (h2 : 21%-31%) and genetically correlated with alcohol dependence (AD) and DSM-IV AD criterion count (rg : 0.35-0.76). Genome-wide significant associations were observed (SRE-T: chromosomes 6, rs140154945, COGA-EA P = 3.30E-08 and 11, rs10647170, COGA-AA+EA P = 3.53E-09; SRE-5: chromosome13, rs4770359, COGA-AA P = 2.92E-08). Chromosome 11 was replicated in an EA dataset from the National Institute on Alcohol Abuse and Alcoholism intramural program. In silico functional analyses and RNA expression analyses suggest that the chromosome 6 locus is an eQTL for KIF25. Polygenic risk scores derived using the COGA SRE-T and SRE-5 GWAS predicted 0.47% to 2.48% of variances in AD and DSM-IV AD criterion count in independent datasets. This study highlights the genetic contribution of alcohol response phenotypes to the etiology of alcohol use disorders. Keywords: RNA expression; genetic correlation; genome-wide association study (GWAS); heritability; polygenic risk score; self-rating of the effects of ethanol (SRE).

Inbred Substrain Differences Influence Neuroimmune Response and Drinking Behavior. - Warden AS,; Da Costa A,; Mason S,; Blednov YA,; Mayfield RD; Harris RA (Alcoholism: Clinical and Experimental Research, 2020)
Background The inbred mouse strain C57BL/6 is widely used in both models of addiction and immunological disease. However, there are pronounced phenotypic differences in ethanol (EtOH) consumption and innate immune response between C57BL/6 substrains. The focus of this study was to examine the effects of substrain on innate immune response and neuroimmune‐induced escalation of voluntary EtOH consumption. The main goal was to identify whether substrain differences in immune response can account for differences in EtOH behavior. Methods We compared acute innate immune response with a viral dsRNA mimic, polyinosinic:polycytidylic acid (poly(I:C)), in brain using qRT‐PCR in both C57BL/6N and C57BL/6J mice. Next, we used a neuroimmune model of escalation using poly(I:C) to compare drinking behavior between substrains. Finally, we compared brain neuroimmune response with both EtOH and repeated poly(I:C) in both substrains as a way to account for differences in EtOH behavior. Results We found that C57BL/6 substrains have differing immune response and drinking behaviors. C57BL/6N mice have a shorter but more robust inflammatory response to acute poly(I:C). In contrast, C57BL/6J mice have a smaller but longer‐lasting acute immune response to poly(I:C). In our neuroimmune‐induced escalation model, C57BL/6J mice but not C57BL/6N mice escalate EtOH intake after poly(I:C). Finally, only C57BL/6J mice show enhanced proinflammatory transcript abundance after poly(I:C) and EtOH, suggesting that longer‐lasting immune responses are critical to neuroimmune drinking phenotypes. Conclusions Altogether, this work has elucidated additional influences that substrain has on both innate immune response and drinking phenotypes. Our observations highlight the importance of considering and reporting the source and background used for production of transgenic and knockout mice. These data provide further evidence that genetic background must be carefully considered when investigating the role of neuroimmune signaling in EtOH abuse.

The inferior colliculus in alcoholism and beyond - Bordia T,; Zahr NM (Front. Syst. Neurosci, 2020)
Post-mortem neuropathological and in vivo neuroimaging methods have demonstrated the vulnerability of the inferior colliculus to the sequelae of thiamine deficiency as occurs in Wernicke-Korsakoff Syndrome (WKS). A rich literature in animal models ranging from mice to monkeys—including our neuroimaging studies in rats—has shown involvement of the inferior colliculi in the neural response to thiamine depletion, frequently accomplished with pyrithiamine, an inhibitor of thiamine metabolism. In uncomplicated alcoholism (i.e., absent diagnosable neurological concomitants), the literature citing involvement of the inferior colliculus is scarce, has nearly all been accomplished in preclinical models, and is predominately discussed in the context of ethanol withdrawal. Our recent work using novel, voxel-based analysis of structural Magnetic Resonance Imaging (MRI) has demonstrated significant, persistent shrinkage of the inferior colliculus using acute and chronic ethanol exposure paradigms in two strains of rats. We speculate that these consistent findings should be considered from the perspective of the inferior colliculi having a relatively high CNS metabolic rate. As such, they are especially vulnerable to hypoxic injury and may be provide a common anatomical link among a variety of disparate insults. An argument will be made that the inferior colliculi have functions, possibly related to auditory gating, necessary for awareness of the external environment. Multimodal imaging including diffusion methods to provide more accurate in vivo visualization and quantification of the inferior colliculi may clarify the roles of brain stem nuclei such as the inferior colliculi in alcoholism and other neuropathologies marked by altered metabolism.

Knock‐in Mice Expressing an Ethanol‐Resistant GluN2A NMDA Receptor Subunit Show Altered Responses to Ethanol - Zamudio PA,; Smothers TC,; Homanics GE,; Woodward JJ (Alcoholism: Clinical and Experimental Research, 2020)
Background N‐methyl‐D‐aspartate receptors (NMDARs) are glutamate‐activated, heterotetrameric ligand‐gated ion channels critically important in virtually all aspects of glutamatergic signaling. Ethanol (EtOH) inhibition of NMDARs is thought to mediate specific actions of EtOH during acute and chronic exposure. Studies from our laboratory, and others, identified EtOH‐sensitive sites within specific transmembrane (TM) domains involved in channel gating as well as those in subdomains of extracellular and intracellular regions of GluN1 and GluN2 subunits that affect channel function. In this study, we characterize for the first time the physiological and behavioral effects of EtOH on knock‐in mice expressing a GluN2A subunit that shows reduced sensitivity to EtOH. Methods A battery of tests evaluating locomotion, anxiety, sedation, motor coordination, and voluntary alcohol intake were performed in wild‐type mice and those expressing the GluN2A A825W knock‐in mutation. Whole‐cell patch‐clamp electrophysiological recordings were used to confirm reduced EtOH sensitivity of NMDAR‐mediated currents in 2 separate brain regions (mPFC and the cerebellum) where the GluN2A subunit is known to contribute to NMDAR‐mediated responses. Results Male and female mice homozygous for the GluN2A(A825W) knock‐in mutation showed reduced EtOH inhibition of NMDAR‐mediated synaptic currents in mPFC and cerebellar neurons as compared to their wild‐type counterparts. GluN2A(A825W) male but not female mice were less sensitive to the sedative and motor‐incoordinating effects of EtOH and showed a rightward shift in locomotor‐stimulating effects of EtOH. There was no effect of the mutation on EtOH‐induced anxiolysis or voluntary EtOH consumption in either male or female mice. Conclusions These findings show that expression of EtOH‐resistant GluN2A NMDARs results in selective and sex‐specific changes in the behavioral sensitivity to EtOH.

Microglia Control Escalation of Drinking in Alcohol-Dependent Mice: Genomic and Synaptic Drivers. - Warden AS,; Wolfe SA,; Khom S,; Varodayan FP; Patel RR,; Steinman MQ,; Bajo M,; Montgomery SE,; Vlkolinsky R,; Nadav T,; Polis I,; Roberts AJ,; et al. (Biological Psychiatry, 2020)
Background Microglia, the primary immune cells of the brain, are implicated in alcohol use disorder. However, it is not known if microglial activation contributes to the transition from alcohol use to alcohol use disorder or is a consequence of alcohol intake. Methods We investigated the role of microglia in a mouse model of alcohol dependence using a colony stimulating factor 1 receptor inhibitor (PLX5622) to deplete microglia and a chronic intermittent ethanol vapor two-bottle choice drinking procedure. Additionally, we examined anxiety-like behavior during withdrawal. We then analyzed synaptic neuroadaptations in the central nucleus of the amygdala (CeA) and gene expression changes in the medial prefrontal cortex and CeA from the same animals used for behavioral studies. Results PLX5622 prevented escalations in voluntary alcohol intake and decreased anxiety-like behavior associated with alcohol dependence. PLX5622 also reversed expression changes in inflammatory-related genes and glutamatergic and GABAergic (gamma-aminobutyric acidergic) genes in the medial prefrontal cortex and CeA. At the cellular level in these animals, microglia depletion reduced inhibitory GABA A and excitatory glutamate receptor-mediated synaptic transmission in the CeA, supporting the hypothesis that microglia regulate dependence-induced changes in neuronal function. Conclusions Our multifaceted approach is the first to link microglia to the molecular, cellular, and behavioral changes associated with the development of alcohol dependence, suggesting that microglia may also be critical for the development and progression of alcohol use disorder.

Mu opioid receptors in the medial habenula contribute to naloxone aversion. - Boulos LJ,; Ben Hamida S,; Bailly J,; Maitra M,; Ehrlich AT,; Gavériaux-Ruff C,; Darcq E,; Kieffer BL., (Neuropsychopharmacology, 2020)
The medial habenula (MHb) is considered a brain center regulating aversive states. The mu opioid receptor (MOR) has been traditionally studied at the level of nociceptive and mesolimbic circuits, for key roles in pain relief and reward processing. MOR is also densely expressed in MHb, however, MOR function at this brain site is virtually unknown. Here we tested the hypothesis that MOR in the MHb (MHb-MOR) also regulates aversion processing. We used chnrb4-Cre driver mice to delete the Oprm1 gene in chnrb4-neurons, predominantly expressed in the MHb. Conditional mutant (B4MOR) mice showed habenula-specific reduction of MOR expression, restricted to chnrb4-neurons (50% MHb-MORs). We tested B4MOR mice in behavioral assays to evaluate effects of MOR activation by morphine, and MOR blockade by naloxone. Locomotor, analgesic, rewarding, and motivational effects of morphine were preserved in conditional mutants. In contrast, conditioned place aversion (CPA) elicited by naloxone was reduced in both naïve (high dose) and morphine-dependent (low dose) B4MOR mice. Further, physical signs of withdrawal precipitated by either MOR (naloxone) or nicotinic receptor (mecamylamine) blockade were attenuated. These data suggest that MORs expressed in MHb B4-neurons contribute to aversive effects of naloxone, including negative effect and aversive effects of opioid withdrawal. MORs are inhibitory receptors, therefore we propose that endogenous MOR signaling normally inhibits chnrb4-neurons of the MHb and moderates their known aversive activity, which is unmasked upon receptor blockade. Thus, in addition to facilitating reward at several brain sites, tonic MOR activity may also limit aversion within the MHb circuitry.

Mu opioid receptors in the medial habenula contribute to naloxone aversion. - Boulos, LJ; Ben Hamida, S; Bailly, J; Maitra, M; Ehrlich, AT; Gavériaux-Ruff, C; Darcq, E; Kieffer, BL (Neuropsychopharmacology, 2020)
The medial habenula (MHb) is considered a brain center regulating aversive states. The mu opioid receptor (MOR) has been traditionally studied at the level of nociceptive and mesolimbic circuits, for key roles in pain relief and reward processing. MOR is also densely expressed in MHb, however, MOR function at this brain site is virtually unknown. Here we tested the hypothesis that MOR in the MHb (MHb-MOR) also regulates aversion processing. We used chnrb4-Cre driver mice to delete the Oprm1 gene in chnrb4-neurons, predominantly expressed in the MHb. Conditional mutant (B4MOR) mice showed habenula-specific reduction of MOR expression, restricted to chnrb4-neurons (50% MHb-MORs). We tested B4MOR mice in behavioral assays to evaluate effects of MOR activation by morphine, and MOR blockade by naloxone. Locomotor, analgesic, rewarding, and motivational effects of morphine were preserved in conditional mutants. In contrast, conditioned place aversion (CPA) elicited by naloxone was reduced in both naïve (high dose) and morphine-dependent (low dose) B4MOR mice. Further, physical signs of withdrawal precipitated by either MOR (naloxone) or nicotinic receptor (mecamylamine) blockade were attenuated. These data suggest that MORs expressed in MHb B4-neurons contribute to aversive effects of naloxone, including negative effect and aversive effects of opioid withdrawal. MORs are inhibitory receptors, therefore we propose that endogenous MOR signaling normally inhibits chnrb4-neurons of the MHb and moderates their known aversive activity, which is unmasked upon receptor blockade. Thus, in addition to facilitating reward at several brain sites, tonic MOR activity may also limit aversion within the MHb circuitry.

Multi-modal imaging reveals differential brain volumetric, biochemical, and white matter fiber responsivity to repeated intermittent ethanol vapor exposure in male and female rats - Zahr NM; Lenart AM,; Karpf JA,; Casey KM,; Pohl KM; Sullivan EV; Pfefferbaum A, (Neuropharmacology, 2020)
A generally accepted framework derived predominately from animal models asserts that repeated cycles of chronic intermittent ethanol (EtOH; CIE) exposure cause progressive brain adaptations associated with anxiety and stress that promote voluntary drinking, alcohol dependence, and further brain changes that contribute to the pathogenesis of alcoholism. The current study used CIE exposure via vapor chambers to test the hypothesis that repeated episodes of withdrawals from chronic EtOH would be associated with accrual of brain damage as quantified using in vivo magnetic resonance imaging (MRI), diffusion tensor imaging (DTI), and MR spectroscopy (MRS). The initial study group included 16 male (~325g) and 16 female (~215g) wild-type Wistar rats exposed to 3 cycles of 1-month in vapor chambers + 1 week of abstinence. Half of each group (n = 8) was given vaporized EtOH to blood alcohol levels approaching 250 mg/dL. Blood and behavior markers were also quantified. There was no evidence for dependence (i.e., increased voluntary EtOH consumption), increased anxiety, or an accumulation of pathology. Neuroimaging brain responses to exposure included increased cerebrospinal fluid (CSF) and decreased gray matter volumes, increased Choline/Creatine, and reduced fimbria-fornix fractional anisotropy (FA) with recovery seen after one or more cycles and effects in female more prominent than in male rats. These results show transient brain integrity changes in response to CIE sufficient to induce acute withdrawal but without evidence for cumulative or escalating damage. Together, the current study suggests that nutrition, age, and sex should be considered when modeling human alcoholism.

PACAP regulation of central amygdala GABAergic synapses is altered by restraint stress. - Varodayan, FP; Minnig, MA; Steinman, MS; Oleata, CS; Riley, MW; Sabino, V; Roberto, M (Neuropharmacology, 2020)
The pituitary adenylate cyclase-activating polypeptide (PACAP) system plays a central role in the brain's emotional response to psychological stress by activating cellular processes and circuits associated with threat exposure. The neuropeptide PACAP and its main receptor PAC1 are expressed in the rodent central amygdala (CeA), a brain region critical in negative emotional processing, and CeA PACAPergic signaling drives anxiogenic and stress coping behaviors. Despite this behavioral evidence, PACAP's effects on neuronal activity within the medial subdivision of the CeA (CeM, the major output nucleus for the entire amygdala complex) during basal conditions and after psychological stress remain unknown. Therefore, in the present study, male Wistar rats were subjected to either restraint stress or control conditions, and PACAPergic regulation of CeM cellular function was assessed using immunohistochemistry and whole-cell patch-clamp electrophysiology. Our results demonstrate that PACAP-38 potentiates GABA release in the CeM of naïve rats, via its actions at presynaptic PAC1. Basal PAC1 activity also enhances GABA release in an action potential-dependent manner. Notably, PACAP-38's facilitation of CeM GABA release was attenuated after a single restraint stress session, but after repeated sessions returned to the level observed in naïve animals. A single restraint session also significantly decreased PAC1 levels in the CeM, with repeated restraint sessions producing a slight recovery. Collectively our data reveal that PACAP/PAC1 signaling enhances inhibitory control of the CeM and that psychological stress can modulate this influence to potentially disinhibit downstream effector regions that mediate anxiety and stress-related behaviors.

PACAP regulation of central amygdala GABAergic synapses is altered by restraint stress. - Varodayan FP; Minnig MA,; Steinman MQ,; Oleata CS,; Riley MW,; Sabino V,; Roberto M (Neuropharmacology, 2020)
The pituitary adenylate cyclase-activating polypeptide (PACAP) system plays a central role in the brain's emotional response to psychological stress by activating cellular processes and circuits associated with threat exposure. The neuropeptide PACAP and its main receptor PAC1 are expressed in the rodent central amygdala (CeA), a brain region critical in negative emotional processing, and CeA PACAPergic signaling drives anxiogenic and stress coping behaviors. Despite this behavioral evidence, PACAP's effects on neuronal activity within the medial subdivision of the CeA (CeM, the major output nucleus for the entire amygdala complex) during basal conditions and after psychological stress remain unknown. Therefore, in the present study, male Wistar rats were subjected to either restraint stress or control conditions, and PACAPergic regulation of CeM cellular function was assessed using immunohistochemistry and whole-cell patch-clamp electrophysiology. Our results demonstrate that PACAP-38 potentiates GABA release in the CeM of naïve rats, via its actions at presynaptic PAC1. Basal PAC1 activity also enhances GABA release in an action potential-dependent manner. Notably, PACAP-38's facilitation of CeM GABA release was attenuated after a single restraint stress session, but after repeated sessions returned to the level observed in naïve animals. A single restraint session also significantly decreased PAC1 levels in the CeM, with repeated restraint sessions producing a slight recovery. Collectively our data reveal that PACAP/PAC1 signaling enhances inhibitory control of the CeM and that psychological stress can modulate this influence to potentially disinhibit downstream effector regions that mediate anxiety and stress-related behaviors. This article is part of the special issue on 'Neuropeptides'. Keywords: Anxiety; GABA; PAC1; PACAP-38; Pituitary adenylate cyclase-activating polypeptide; Synaptic transmission; sIPSC.

Perineuronal nets in the insula regulate aversion-resistant alcohol drinking. - Chen, H; Lasek, AW (Addict Biol., 2020)
One of the most pernicious characteristics of alcohol use disorder is the compulsion to drink despite negative consequences. The insular cortex controls decision making under conditions of risk or conflict. Cortical activity is tightly controlled by inhibitory interneurons that are often enclosed by specialized extracellular matrix structures known as perineuronal nets (PNNs), which regulate neuronal excitability and plasticity. The density of PNNs in the insula increases after repeated bouts of binge drinking, suggesting that they may play a role in the transition from social to compulsive, or aversion-resistant, drinking. Here, we investigated whether insular PNNs play a role in aversion-resistant alcohol drinking using a mouse model in which ethanol was adulterated with the bitter tastant quinine. Disrupting PNNs in the insula rendered mice more sensitive to quinine-adulterated ethanol but not ethanol alone. Activation of the insula, as measured by c-fos expression, occurred during aversion-resistant drinking and was further enhanced by elimination of PNNs. These results demonstrate that PNNs control the activation of the insula during aversion-resistant drinking and suggest that proper excitatory/inhibitory balance is important for decision making under conditions of conflict. Disrupting PNNs in the insula or optimizing insula activation may be a novel strategy to reduce aversion-resistant drinking.

Phenotypic and gene expression features associated with variation in chronic ethanol consumption in heterogeneous stock collaborative cross mice. - Hitzemann R,; Phillips TJ,; Lockwood DR,; Darakjian P,; Searles RP, (Genomics, 2020)
Of the more than 100 studies that have examined relationships between excessive ethanol consumption and the brain transcriptome, few rodent studies have examined chronic consumption. Heterogeneous stock collaborative cross mice freely consumed ethanol vs. water for 3 months. Transcriptional differences were examined for the central nucleus of the amygdala, a brain region known to impact ethanol preference. Early preference was modestly predictive of final preference and there was significant escalation of preference in females only. Genes significantly correlated with female preference were enriched in annotations for the primary cilium and extracellular matrix. A single module in the gene co-expression network was enriched in genes with an astrocyte annotation. The key hub node was the master regulator, orthodenticle homeobox 2 (Otx2). These data support an important role for the extracellular matrix, primary cilium and astrocytes in ethanol preference and consumption differences among individual female mice of a genetically diverse population.

Receptor tyrosine kinases as therapeutic targets for alcohol use disorder. Neurotherapeutics. - Hamada, K; Lasek, AW (Neurotherapeutics, 2020)
The receptor tyrosine kinases (RTKs) are a large family of proteins that transduce extracellular signals to the inside of the cell to ultimately affect important cellular functions such as cell proliferation, survival, apoptosis, differentiation, and migration. They are expressed in the nervous system and can regulate behavior through modulation of neuronal and glial function. As a result, RTKs are implicated in neurodegenerative and psychiatric disorders such as depression and addiction. Evidence has emerged that 5 RTKs (tropomyosin-related kinase B (TrkB), RET proto-oncogene (RET), anaplastic lymphoma kinase (ALK), fibroblast growth factor receptor (FGFR), and epidermal growth factor receptor (EGFR)) modulate alcohol drinking and other behaviors related to alcohol addiction. RTKs are considered highly "druggable" targets and small-molecule inhibitors of RTKs have been developed for the treatment of various conditions, particularly cancer. These kinases are therefore attractive targets for the development of new pharmacotherapies to treat alcohol use disorder (AUD). This review will examine the preclinical evidence describing TrkB, RET, ALK, FGFR, and EGFR modulation of alcohol drinking and other behaviors relevant to alcohol abuse.

Regulation of the deleterious effects of binge-like exposure to alcohol during adolescence by α7 nicotinic acetylcholine receptor agents: prevention by pretreatment with a α7 negative allosteric modulator and emulation by a α7 agonist in alcohol-prefer - Rodd ZA; Hauser SR,; Swartzwelder HS,; Waeiss RA,; Lahiri DK,; Bell RL, (Psychopharmacology, 2020)
Rationale and objectives: Binge-like alcohol consumption during adolescence associates with several deleterious consequences during adulthood including an increased risk for developing alcohol use disorder (AUD) and other addictions. Replicated preclinical data has indicated that adolescent exposure to binge-like levels of alcohol results in a reduction of choline acetyltransferase (ChAT) and an upregulation in the α7 nicotinic receptor (α7). From this information, we hypothesized that the α7 plays a critical role in mediating the effects of adolescent alcohol exposure. Methods: Male and female P rats were injected with the α7 agonist AR-R17779 (AR) once during 6 time points between post-natal days (PND) 29-37. Separate groups were injected with the α7 negative allosteric modulator (NAM) dehydronorketamine (DHNK) 2 h before administration of 4 g/kg EtOH (14 total exposures) during PND 28-48. On PND 75, all rats were given access to water and ethanol (15 and 30%) for 6 consecutive weeks (acquisition). All rats were then deprived of EtOH for 2 weeks and then, alcohol was returned (relapse). Results: Administration of AR during adolescence significantly increased acquisition of alcohol consumption during adulthood and prolonged relapse drinking in P rats. In contrast, administration of DHNK prior to binge-like EtOH exposure during adolescence prevented the increase in alcohol consumption observed during acquisition of alcohol consumption and the enhancement of relapse drinking observed during adulthood. Discussion: The data indicate that α7 mediates the effects of alcohol during adolescence. The data also indicate that α7 NAMs are potential prophylactic agents to reduce the deleterious effects of adolescent alcohol abuse. Keywords: Acquisition; Addiction; Adolescence; Alcohol; Alcohol-preferring (P) rats; Ethanol; Relapse.

The rewarding and anxiolytic properties of ethanol within the central nucleus of the amygdala: mediated by genetic background and nociceptin. - Knight CP,; Hauser SR,; Waeiss RA,; Molosh AI,; Johnson PL,; Truitt WA,; McBride WJ,; Bell RL,; Shekhar A,; Rodd ZA (Journal of Pharmacology and Experimental Therapeutics, 2020)
In humans, alcohol is consumed for its rewarding and anxiolytic effects. The Central Nucleus of the Amygdala (CeA) is considered a neuronal nexus that regulates fear, anxiety and drug self-administration. Manipulations of the CeA alter ethanol (EtOH) consumption under numerous EtOH self-administration models. The experiments determined if EtOH is reinforcing/anxiolytic within the CeA, if selective breeding for high alcohol consumption alters the rewarding properties of EtOH in the CeA, and if the reinforcing/anxiolytic effects of EtOH in the CeA are mediated by the neuropeptides corticotropin-releasing factor (CRF) and nociceptin. The reinforcing properties of EtOH were determined by having male Wistar and Taconic Alcohol-Preferring (tP) rats self-administer EtOH directly into the CeA. The expression of anxiety-like behaviors was assessed through multiple behavioral models (social interaction, acoustic startle, open field). Co-administration of EtOH and a CRF1 antagonist (NBI 35965) or nociceptin on self-administration into the CeA and anxiety-like behaviors was determined. EtOH was self-administered directly into the lateral CeA and tP rats self-administered a lower concentration of EtOH than Wistar rats. EtOH microinjected into the lateral CeA reduced the expression of anxiety-like behaviors, indicating an anxiolytic effect. The co-administration of NBI 35965 failed to alter the rewarding/anxiolytic properties of EtOH in the CeA. In contrast, co-administration of the nociceptin enhanced both EtOH reward and anxiolysis in the CeA. The data indicate that the lateral CeA is a key anatomical location that mediates the rewarding and anxiolytic effects of EtOH and activation of nociceptin receptors augment the effects of EtOH in this region. SIGNIFICANCE STATEMENT Alcohol is consumed for the stimulatory, rewarding, and anxiolytic properties of the drug of abuse. The current data are the first to establish that alcohol is reinforcing and anxiolytic within the lateral central nucleus of the amygdala (CeA), and that the Nociceptin system regulates these effects of alcohol within the CeA.

Role of toll-like receptor 7 (TLR7) in voluntary alcohol consumption - Grantham EK,; Warden AS,; McCarthy GS,; Da Costa A,; Mason S,; Blednov Y,; Mayfield RD; Harris RA. (Brain, Behavior, and Immunity, 2020)
Overactivation of neuroimmune signaling has been linked to excessive ethanol consumption. Toll-like receptors (TLRs) are a major component of innate immune signaling and initiate anti- and pro-inflammatory responses via intracellular signal transduction cascades. TLR7 is upregulated in post-mortem brain tissue from humans with alcohol use disorder (AUD) and animals with prior exposure to ethanol. Despite this evidence, the role of TLR7 in the regulation of voluntary ethanol consumption has not been studied. We test the hypothesis that TLR7 activation regulates voluntary ethanol drinking behavior by administering a TLR7 agonist (R848) during an intermittent access drinking procedure in mice. Acute activation of TLR7 reduced ethanol intake, preference, and total fluid intake due, at least in part, to an acute sickness response. However, chronic pre-treatment with R848 resulted in tolerance to the adverse effects of the drug and a subsequent increase in ethanol consumption. To determine the molecular machinery that mediates these behavioral changes, we evaluated gene expression after acute and chronic TLR7 activation. We found that acute TLR7 activation produces brain region specific changes in expression of immune pathway genes, whereas chronic TLR7 activation causes downregulation of TLRs and blunted cytokine induction, suggesting molecular tolerance. Our results demonstrate a novel role for TLR7 signaling in regulating voluntary ethanol consumption. Taken together, our findings suggest TLR7 may be a viable target for development of therapies to treat AUD.

Role of toll-like receptor 7 (TLR7) in voluntary alcohol consumption. - Grantham EK,; Warden AS,; McCarthy GS,; Da Costa A,; Mason S,; Blednov Y,; Mayfield RD; Harris RA (Brain Behavior and Immunity, 2020)
Overactivation of neuroimmune signaling has been linked to excessive ethanol consumption. Toll-like receptors (TLRs) are a major component of innate immune signaling and initiate anti- and pro-inflammatory responses via intracellular signal transduction cascades. TLR7 is upregulated in post-mortem brain tissue from humans with alcohol use disorder (AUD) and animals with prior exposure to ethanol. Despite this evidence, the role of TLR7 in the regulation of voluntary ethanol consumption has not been studied. We test the hypothesis that TLR7 activation regulates voluntary ethanol drinking behavior by administering a TLR7 agonist (R848) during an intermittent access drinking procedure in mice. Acute activation of TLR7 reduced ethanol intake, preference, and total fluid intake due, at least in part, to an acute sickness response. However, chronic pre-treatment with R848 resulted in tolerance to the adverse effects of the drug and a subsequent increase in ethanol consumption. To determine the molecular machinery that mediates these behavioral changes, we evaluated gene expression after acute and chronic TLR7 activation. We found that acute TLR7 activation produces brain region specific changes in expression of immune pathway genes, whereas chronic TLR7 activation causes downregulation of TLRs and blunted cytokine induction, suggesting molecular tolerance. Our results demonstrate a novel role for TLR7 signaling in regulating voluntary ethanol consumption. Taken together, our findings suggest TLR7 may be a viable target for development of therapies to treat AUD.

Selective breeding for high alcohol preference is associated with increased sensitivity to cannabinoid reward within the nucleus accumbens shell. - Hauser SR,; Katner SN,; Waeiss RA,; Truitt WA,; Bell RL,; McBride WJ,; Rodd ZA (Pharmacology Biochemistry and Behavior, 2020)
Rationale The rate of cannabinoid intake by those with alcohol use disorder (AUD) exceeds that of the general public. The high prevalence of co-abuse of alcohol and cannabis has been postulated to be predicated upon both a common predisposing genetic factor and the interaction of the drugs within the organism. The current experiments examined the effects of cannabinoids in an animal model of AUD. Objectives The present study assessed the reinforcing properties of a cannabinoid receptor 1 (CB1) agonist self-administered directly into the nucleus accumbens shell (AcbSh) in female Wistar and alcohol-preferring (P) rats. Methods Following guide cannulae surgery aimed at AcbSh, subjects were placed in an operant box equipped with an ‘active lever’ (fixed ratio 1; FR1) that caused the delivery of the infusate and an ‘inactive lever’ that did not. Subjects were arbitrarily assigned to one of seven groups that self-administered either artificial cerebrospinal fluid (aCSF), or 3.125, 6.25, 12.5, or 25 pmol/100 nl of O-1057, a water-soluble CB1 agonist, dissolved in aCSF. The first four sessions of acquisition are followed by aCSF only infusates in sessions 5 and 6 during extinction, and finally the acquisition dose of infusate during session 7 as reinstatement. Results The CB1 agonist was self-administered directly into the AcbSh. P rats self-administered the CB1 agonist at lower concentrations and at higher rates compared to Wistar rats. Conclusions Overall, the data indicate selective breeding for high alcohol preference has produced rats divergent in response to cannabinoids within the brain reward pathway. The data support the hypothesis that there can be common genetic factors influencing drug addiction.

Single cell transcriptome profiling of the human alcohol-dependent brain - Brenner E,; Tiwari GR,; Kapoor M,; Liu Y,; Brock A,; Mayfield RD (Human Molecular Genetics, 2020)
Alcoholism remains a prevalent health concern throughout the world. Previous studies have identified transcriptomic patterns in the brain associated with alcohol dependence in both humans and animal models. But none of these studies have systematically investigated expression within the unique cell types present in the brain. We utilized single nucleus RNA sequencing (snRNA-seq) to examine the transcriptomes of over 16 000 nuclei isolated from the prefrontal cortex of alcoholic and control individuals. Each nucleus was assigned to one of seven major cell types by unsupervised clustering. Cell type enrichment patterns varied greatly among neuroinflammatory-related genes, which are known to play roles in alcohol dependence and neurodegeneration. Differential expression analysis identified cell type-specific genes with altered expression in alcoholics. The largest number of differentially expressed genes (DEGs), including both protein-coding and non-coding, were detected in astrocytes, oligodendrocytes and microglia. To our knowledge, this is the first single cell transcriptome analysis of alcohol-associated gene expression in any species and the first such analysis in humans for any addictive substance. These findings greatly advance the understanding of transcriptomic changes in the brain of alcohol-dependent individuals.

The SMYD1 and skNAC transcription factors contribute to neurodegenerative diseases. - Mayfield RD; Zhu L,; Smith TA,; Tiwari GR,; Tucker HO. (Brain, behavior, & immunity - health, 2020)
SMYD1 and the skNAC isoform of the NAC transcription factor have both previously been characterized as transcription factors in hematopoiesis and cardiac/skeletal muscle. Here we report that comparative analysis of genes deregulated by SMYD1 or skNAC knockdown in differentiating C2C12 myoblasts identified transcripts characteristic of neurodegenerative diseases, including Alzheimer's, Parkinson's and Huntington's Diseases (AD, PD, and HD). This led us to determine whether SMYD1 and skNAC function together or independently within the brain. Based on meta-analyses and direct experimentation, we observed SMYD1 and skNAC expression within cortical striata of human brains, mouse brains and transgenic mouse models of these diseases. We observed some of these features in mouse myoblasts induced to differentiate into neurons. Finally, several defining features of Alzheimer's pathology, including the brain-specific, axon-enriched microtubule-associated protein, Tau, are deregulated upon SMYD1 loss. Keywords: Neuroinflammatory disease; SMYD1 and skNAC; Transcriptional regulation.

Spontaneous early withdrawal behaviors after chronic 24-hour free-choice access to ethanol. - Hauser SR,; Smith RJ,; Toalston JE,; Rodd ZA; McBride WJ,; Bell RL, (Alcohol and Alcoholism, 2020)
Aims Abstinence after chronic alcohol consumption leads to withdrawal symptoms, which are exacerbated after repeated cycles of relapse. This study examined withdrawal-like behaviors after chronic ethanol drinking, with or without repeated cycles of deprivation. Methods Male alcohol-preferring (P) rats had access to continuous ethanol (CE), chronic ethanol with repeated deprivation (RD), or remained ethanol naïve (EN). The RD group experienced seven cycles of 2 weeks of deprivation and 2 weeks of re-exposure to ethanol after an initial 6 weeks of ethanol access. Withdrawal was measured after an initial 24 h of ethanol re-exposure in the RD group, which coincided with the same day of ethanol access in the CE group. Withdrawal-like behavior was measured by (a) ethanol intake during the initial 24 h of re-exposure, (b) locomotor activity (LMA) in a novel field 9–13 h after removal of ethanol at the beginning of the fifth re-exposure cycle and (c) acoustic startle responding (ASR) 8–15 h after removal of ethanol at the beginning of the sixth re-exposure cycle. Results The RD rats displayed a 1-h alcohol deprivation effect (ADE) (temporary ethanol increase), relative to CE rats, during the first to fourth and seventh re-exposure cycles. RD and CE rats displayed significant increases in LMA than EN rats. Regarding ASR, RD rats displayed significantly greater ASR relative to EN rats. Conclusion This study confirms that P rats meet the animal model criterion for ethanol-associated dependence, without a reliance on either behavioral (limited fluid access) or pharmacological (seizure threshold manipulation) challenges.

Spontaneous early withdrawal behaviors after chronic 24-hour free-choice access to ethanol - Hauser SR,; Smith RJ,; Toalston JE,; Rodd ZA; McBride WJ,; Bell RL, (Alcohol and Alcoholism, 2020)
Aims: Abstinence after chronic alcohol consumption leads to withdrawal symptoms, which are exacerbated after repeated cycles of relapse. This study examined withdrawal-like behaviors after chronic ethanol drinking, with or without repeated cycles of deprivation. Methods: Male alcohol-preferring (P) rats had access to continuous ethanol (CE), chronic ethanol with repeated deprivation (RD), or remained ethanol naïve (EN). The RD group experienced seven cycles of 2 weeks of deprivation and 2 weeks of re-exposure to ethanol after an initial 6 weeks of ethanol access. Withdrawal was measured after an initial 24 h of ethanol re-exposure in the RD group, which coincided with the same day of ethanol access in the CE group. Withdrawal-like behavior was measured by (a) ethanol intake during the initial 24 h of re-exposure, (b) locomotor activity (LMA) in a novel field 9-13 h after removal of ethanol at the beginning of the fifth re-exposure cycle and (c) acoustic startle responding (ASR) 8-15 h after removal of ethanol at the beginning of the sixth re-exposure cycle. Results: The RD rats displayed a 1-h alcohol deprivation effect (ADE) (temporary ethanol increase), relative to CE rats, during the first to fourth and seventh re-exposure cycles. RD and CE rats displayed significant increases in LMA than EN rats. Regarding ASR, RD rats displayed significantly greater ASR relative to EN rats. Conclusion: This study confirms that P rats meet the animal model criterion for ethanol-associated dependence, without a reliance on either behavioral (limited fluid access) or pharmacological (seizure threshold manipulation) challenges.

Structural and biochemical imaging reveals systemic LPS-induced changes in the rat brain - Fritz M; Klawonn AM,; Zhao Q; Sullivan EV; Zahr NM; Pfefferbaum A, (J Neuroimmunol, 2020)
Despite mounting evidence for the role of inflammation in Major Depressive Disorder (MDD), in vivo preclinical investigations of inflammation-induced negative affect using whole brain imaging modalities are scarce, precluding a valid model within which to evaluate pharmacological interventions. Here we used an E. coli lipopolysaccharide (LPS)-based model of inflammation-induced depressive signs in rats to explore brain changes using multimodal neuroimaging methods. During the acute phase of the LPS response (2 h post injection), prior to the emergence of a task-quantifiable depressive phenotype, striatal glutamine levels and splenial, retrosplenial, and peri-callosal hippocampal cortex volumes were greater than at baseline. LPS-induced depressive behaviors observed at 24 h, however, occurred concurrently with lower than control levels of striatal glutamine and a reversibility of volume expansion (i.e., shrinkage of splenial, retrosplenial, and peri-callosal hippocampal cortex to baseline volumes). In both striatum and hippocampus at 24 h, mRNA expression in LPS relative to control animals demonstrated alterations in enzymes and transporters regulating glutamine homeostasis. Collectively, the observed behavioral, in vivo structural and metabolic, and mRNA expression alterations suggest a critical role for astrocytic regulation of inflammation-induced depressive behaviors.

Targeting morphine-responsive neurons: generation of a knock-in mouse line expressing Cre recombinase from the mu-opioid receptor gene locus - Bailly J,; Del Rossi N,; Runtz L,; Li JJ,; Park D,; Scherrer G,; Tanti A,; Birling MC,; Darcq E,; Kieffer BL, (eNeuro, 2020)
The mu-opioid receptor (MOR) modulates nociceptive pathways and reward processing, and mediates the strong analgesic and addictive properties of both medicinal as well as abused opioid drugs. MOR function has been extensively studied, and tools to manipulate or visualize the receptor protein are available. However, circuit mechanisms underlying MOR-mediated effects are less known, because genetic access to MOR-expressing neurons is lacking. Here we report the generation of a knock-in Oprm1-Cre mouse line, which allows targeting and manipulating MOR opioid-responsive neurons. A cDNA encoding a T2A cleavable peptide and Cre recombinase fused to enhanced green fluorescent protein (EGFP/Cre) was inserted downstream of the Oprm1 gene sequence. The resulting Oprm1-Cre line shows intact Oprm1 gene transcription. MOR and EGFP/Cre proteins are coexpressed in the same neurons, and localized in cytoplasmic and nuclear compartments, respectively. MOR signaling is unaltered, demonstrated by maintained DAMGO-induced G-protein activation, and in vivo MOR function is preserved as indicated by normal morphine-induced analgesia, hyperlocomotion, and sensitization. The Cre recombinase efficiently drives the expression of Cre-dependent reporter genes, shown by local virally mediated expression in the medial habenula and brain-wide fluorescence on breeding with tdTomato reporter mice, the latter showing a distribution patterns typical of MOR expression. Finally, we demonstrate that optogenetic activation of MOR neurons in the ventral tegmental area of Oprm1-Cre mice evokes strong avoidance behavior, as anticipated from the literature. The Oprm1-Cre line is therefore an excellent tool for both mapping and functional studies of MOR-positive neurons, and will be of broad interest for opioid, pain, and addiction research.

Targeting the glucocorticoid receptor reduces binge-like drinking in high drinking in the dark (HDID-1) mice - Savarese AM,; Ozburn AR,; Metten P,; Schlumbohm JP,; Hack WR,; LeMoine K,; Hunt H,; Hausch F,; Bauder M,; Crabbe JC, (Alcohol Clin Exp Res, 2020)
Background: Chronic alcohol exposure can alter glucocorticoid receptor (GR) function in some brain areas that promotes escalated and compulsive-like alcohol intake. GR antagonism can prevent dependence-induced escalation in drinking, but very little is known about the role of GR in regulating high-risk nondependent alcohol intake. Here, we investigate the role of GR in regulating binge-like drinking and aversive responses to alcohol in the High Drinking in the Dark (HDID-1) mice, which have been selectively bred for high blood ethanol (EtOH) concentrations (BECs) in the Drinking in the Dark (DID) test, and in their founder line, the HS/NPT. Methods: In separate experiments, male and female HDID-1 mice were administered one of several compounds that inhibited GR or its negative regulator, FKBP51 (mifepristone [12.5, 25, 50, 100 mg/kg], CORT113176 [20, 40, 80 mg/kg], and SAFit2 [10, 20, 40 mg/kg]) during a 2-day DID task. EtOH consumption and BECs were measured. EtOH conditioned taste and place aversion (CTA and CPA, respectively) were measured in separate HDID-1 mice after mifepristone administration to assess GR's role in regulating the conditioned aversive effects of EtOH. Lastly, HS/NPT mice were administered CORT113176 during DID to assess whether dissimilar effects from those of HDID-1 would be observed, which could suggest that selective breeding had altered sensitivity to the effects of GR antagonism on binge-like drinking. Results: GR antagonism (with both mifepristone and CORT113176) selectively reduced binge-like EtOH intake and BECs in the HDID-1 mice, while inhibition of FKBP51 did not alter intake or BECs. In contrast, GR antagonism had no effect on EtOH intake or BECs in the HS/NPT mice. Although HDID-1 mice exhibit attenuated EtOH CTA, mifepristone administration did not enhance the aversive effects of EtOH in either a CTA or CPA task. Conclusion: These data suggest that the selection process increased sensitivity to GR antagonism on EtOH intake in the HDID-1 mice, and support a role for the GR as a genetic risk factor for high-risk alcohol intake. Keywords: Alcohol; Aversion; Binge Drinking; FKBP51; Glucocorticoid Receptor.

Targeting the Glucocorticoid Receptor Reduces Binge‐Like Drinking in High Drinking in the Dark (HDID‐1) Mice - Savarese AM,; Ozburn AR,; Metten P,; Schlumbohm JP,; Hack WR,; LeMoine K,; Hunt H,; Hausch F,; Bauder M,; Crabbe JC, (Alcoholism: Clinical and Experimental Research, 2020)
Background Chronic alcohol exposure can alter glucocorticoid receptor (GR) function in some brain areas that promotes escalated and compulsive‐like alcohol intake. GR antagonism can prevent dependence‐induced escalation in drinking, but very little is known about the role of GR in regulating high‐risk nondependent alcohol intake. Here, we investigate the role of GR in regulating binge‐like drinking and aversive responses to alcohol in the High Drinking in the Dark (HDID‐1) mice, which have been selectively bred for high blood ethanol (EtOH) concentrations (BECs) in the Drinking in the Dark (DID) test, and in their founder line, the HS/NPT. Methods In separate experiments, male and female HDID‐1 mice were administered one of several compounds that inhibited GR or its negative regulator, FKBP51 (mifepristone [12.5, 25, 50, 100 mg/kg], CORT113176 [20, 40, 80 mg/kg], and SAFit2 [10, 20, 40 mg/kg]) during a 2‐day DID task. EtOH consumption and BECs were measured. EtOH conditioned taste and place aversion (CTA and CPA, respectively) were measured in separate HDID‐1 mice after mifepristone administration to assess GR’s role in regulating the conditioned aversive effects of EtOH. Lastly, HS/NPT mice were administered CORT113176 during DID to assess whether dissimilar effects from those of HDID‐1 would be observed, which could suggest that selective breeding had altered sensitivity to the effects of GR antagonism on binge‐like drinking. Results GR antagonism (with both mifepristone and CORT113176) selectively reduced binge‐like EtOH intake and BECs in the HDID‐1 mice, while inhibition of FKBP51 did not alter intake or BECs. In contrast, GR antagonism had no effect on EtOH intake or BECs in the HS/NPT mice. Although HDID‐1 mice exhibit attenuated EtOH CTA, mifepristone administration did not enhance the aversive effects of EtOH in either a CTA or CPA task. Conclusion These data suggest that the selection process increased sensitivity to GR antagonism on EtOH intake in the HDID‐1 mice, and support a role for the GR as a genetic risk factor for high‐risk alcohol intake.

Taurine Suppression of Central Amygdala GABAergic Inhibitory Signaling via Glycine Receptors Is Disrupted in Alcohol Dependence - Kirson D,; Oleata CS,; Roberto M (Alcoholism: Clinical and Experimental Research, 2020)
Background Alcohol use disorder (AUD) increases brain stress systems while suppressing reward system functioning. One expression of stress system recruitment is elevated GABAergic activity in the central amygdala (CeA), which is involved in the excessive drinking seen with AUD. The sulfonic amino acid taurine, a glycine receptor partial agonist, modulates GABAergic activity in the rewarding effects of alcohol. Despite taurine abundance in the amygdala, its role in the dysregulation of GABAergic activity associated with AUD has not been studied. Thus, here, we evaluated the effects of taurine on locally stimulated GABAergic neurotransmission in the CeA of naïve‐ and alcohol‐dependent rats. Methods We recorded intracellularly from CeA neurons of naïve‐ and alcohol‐dependent rats, quantifying locally evoked GABAA receptor‐mediated inhibitory postsynaptic potentials (eIPSP). We examined the effects of taurine and alcohol on CeA eIPSP to characterize potential alcohol dependence‐induced changes in the effects of taurine. Results We found that taurine decreased amplitudes of eIPSP in CeA neurons of naïve rats, without affecting the acute alcohol‐induced facilitation of GABAergic responses. In CeA neurons from dependent rats, taurine no longer had an effect on eIPSP, but now blocked the ethanol (EtOH)‐induced increase in eIPSP amplitude normally seen. Additionally, preapplication of the glycine receptor‐specific antagonist strychnine blocked the EtOH‐induced increase in eIPSP amplitude in neurons from naïve rats. Conclusions These data suggest taurine may act to oppose the effects of acute alcohol via the glycine receptor in the CeA of naïve rats, and this modulatory system is altered in the CeA of dependent rats.

Transcriptome Analysis of Alcohol Drinking in Non-Dependent and Dependent Mice Following Repeated Cycles of Forced Swim Stress Exposure. - Farris SP,; Tiwari GR,; Ponomareva O,; Lopez MF,1; Mayfield RD; Becker HC. (Brain sciences, 2020)
Chronic stress is a known contributing factor to the development of drug and alcohol addiction. Animal models have previously shown that repeated forced swim stress promotes escalated alcohol consumption in dependent animals. To investigate the underlying molecular adaptations associated with stress and chronic alcohol exposure, RNA-sequencing and bioinformatics analyses were conducted on the prefrontal cortex (CTX) of male C57BL/6J mice that were behaviorally tested for either non-dependent alcohol consumption (CTL), chronic intermittent ethanol (CIE) vapor dependent alcohol consumption, repeated bouts of forced swim stress alone (FSS), and chronic intermittent ethanol with forced swim stress (CIE + FSS). Brain tissue from each group was collected at 0-h, 72-h, and 168-h following the final test to determine long-lasting molecular changes associated with maladaptive behavior. Our results demonstrate unique temporal patterns and persistent changes in coordinately regulated gene expression systems with respect to the tested behavioral group. For example, increased expression of genes involved in "transmitter-gated ion channel activity" was only determined for CIE + FSS. Overall, our results provide a summary of transcriptomic adaptations across time within the CTX that are relevant to understanding the neurobiology of chronic alcohol exposure and stress. Keywords: RNA-Sequencing; alcohol drinking; dependence; mouse; prefrontal cortex; stress.

Why timing matters in alcohol use disorder recovery. - Sullivan EV (American Journal of Psychiatry, 2020)

Tetracycline derivatives reduce binge alcohol consumption in High Drinking in the Dark mice. - Crabbe JC,; Ozburn AR,; Hitzemann RJ,; Spence SE,; Hack WR,; Schlumbohm JP,; Metten P, (Brain, Behaviour and Immunity, 2020)
Alcohol use disorders (AUDs) are prevalent, and are characterized by binge-like drinking, defined by patterns of focused drinking where dosages ingested in 2–4 ​h reach intoxicating blood alcohol levels (BALs). Current medications are few and compliance with the relatively rare prescribed usage is low. Hence, novel and more effective medications are needed. We developed a mouse model of genetic risk for binge drinking (HDID: High Drinking in the Dark mice) by selectively breeding for high BALs after binge drinking. A transcriptional analysis of HDID brain tissue with RNA-Seq implicated neuroinflammatory mechanisms, and, more specifically extracellular matrix genes, including those encoding matrix metalloproteinases (MMPs). Prior experiments from other groups have shown that the tetracycline derivatives doxycycline, minocycline, and tigecycline, reduce binge drinking in inbred C57BL/6J mice. We tested these three compounds in female and male HDID mice and found that all three reduced DID and BAL. They had drug-specific effects on intake of water or saccharin in the DID assay. Thus, our results show that the effectiveness of synthetic tetracycline derivatives as potential therapeutic agents for AUDs is not limited to the single C57BL/6J genotype previously targeted, but extends to a mouse model of a population at high risk for AUDs.

Adolescent intermittent ethanol increases the sensitivity to the reinforcing properties of ethanol and the expression of select cholinergic and dopaminergic genes within the posterior ventral tegmental area. - Hauser, SR; Knight, CP; Truitt, WA; Waeiss, RA; Holt, IS; Carvajal, GB; Bell, RL; Rodd, ZA (Alcoholism: Clinical and Experimental Research, 2019)
Background Although not legally allowed to consume alcohol, adolescents account for 11% of all alcohol use in the United States and approximately 90% of adolescent intake is in the form of an alcohol binge. The adolescent intermittent ethanol (AIE) model developed by the NADIA consortium produces binge‐like EtOH exposure episodes. The current experiment examined the effects of AIE on the reinforcing properties of EtOH and genetic expression of cholinergic and dopaminergic factors within the posterior ventral tegmental area (pVTA) in Wistar male and female rats and in male alcohol‐preferring (P) rats. Methods Rats were exposed to the AIE or water during adolescence, and all testing occurred during adulthood. Wistar control and AIE rats were randomly assigned to groups that self‐administered 0 to 200 mg% EtOH. Male P rats self‐administered 0 to 100 mg%. Results The data indicated that exposure to AIE in both Wistar male and female rats (and male P rats) resulted in a significant leftward shift in dose–response curve for EtOH self‐administration into the pVTA. TaqMan array indicated that AIE exposure had divergent effects on the expression of nicotinic receptors (increased a7, reduction in a4 and a5). There were also sex‐specific effects of AIE on gene expression; male only reduction in D3 receptors. Conclusion Binge‐like EtOH exposure during adolescence enhances the sensitivity to the reinforcing properties of EtOH during adulthood which could be part of biological sequelae that are the basis for the deleterious effects of adolescent alcohol consumption on the rate of alcoholism during adulthood.

Adolescent Intermittent Ethanol Increases the Sensitivity to the Reinforcing Properties of Ethanol and the Expression of Select Cholinergic and Dopaminergic Genes within the Posterior Ventral Tegmental Area - Hauser SR,; Knight CP,; Truitt WA,; Waeiss RA,; Holt IS,; Carvajal GB,; Bell RL,; Rodd ZA (Alcoholism: Clinical and Experimental Research, 2019)
Background Although not legally allowed to consume alcohol, adolescents account for 11% of all alcohol use in the United States and approximately 90% of adolescent intake is in the form of an alcohol binge. The adolescent intermittent ethanol (AIE) model developed by the NADIA consortium produces binge‐like EtOH exposure episodes. The current experiment examined the effects of AIE on the reinforcing properties of EtOH and genetic expression of cholinergic and dopaminergic factors within the posterior ventral tegmental area (pVTA) in Wistar male and female rats and in male alcohol‐preferring (P) rats. Methods Rats were exposed to the AIE or water during adolescence, and all testing occurred during adulthood. Wistar control and AIE rats were randomly assigned to groups that self‐administered 0 to 200 mg% EtOH. Male P rats self‐administered 0 to 100 mg%. Results The data indicated that exposure to AIE in both Wistar male and female rats (and male P rats) resulted in a significant leftward shift in dose–response curve for EtOH self‐administration into the pVTA. TaqMan array indicated that AIE exposure had divergent effects on the expression of nicotinic receptors (increased a7, reduction in a4 and a5). There were also sex‐specific effects of AIE on gene expression; male only reduction in D3 receptors. Conclusion Binge‐like EtOH exposure during adolescence enhances the sensitivity to the reinforcing properties of EtOH during adulthood which could be part of biological sequelae that are the basis for the deleterious effects of adolescent alcohol consumption on the rate of alcoholism during adulthood.

Age-dependent impairment of metabotropic glutamate receptor 2-dependent long-term depression in the mouse striatum by chronic ethanol exposure - Johnson KA,; Liput DJ,; Homanics GE,; Lovinger DM (Alcohol, 2019)
Chronic alcohol exposure is associated with increased reliance on behavioral strategies involving the dorsolateral striatum (DLS), including habitual or stimulus-response behaviors. Presynaptic G protein-coupled receptors (GPCRs) on cortical and thalamic inputs to the DLS inhibit glutamate release, and alcohol-induced disruption of presynaptic GPCR function represents a mechanism by which alcohol could disinhibit DLS neurons and thus bias toward use of DLS-dependent behaviors. Metabotropic glutamate receptor 2 (mGlu2) is a Gi/o-coupled GPCR that robustly modulates glutamate transmission in the DLS, inducing long-term depression (LTD) at both cortical and thalamic synapses. Loss of mGlu2 function has recently been associated with increased ethanol seeking and consumption, but the ability of alcohol to produce adaptations in mGlu2 function in the DLS has not been investigated. We exposed male C57Bl/6J mice to a 2-week chronic intermittent ethanol (CIE) paradigm followed by a brief withdrawal period, then used whole-cell patch clamp recordings of glutamatergic transmission in the striatum to assess CIE effects on mGlu2-mediated synaptic plasticity. We report that CIE differentially disrupts mGlu2-mediated long-term depression in the DLS vs. dorsomedial striatum (DMS). Interestingly, CIE-induced impairment of mGlu2-LTD in the dorsolateral striatum is only observed when alcohol exposure occurs during adolescence. Incubation of striatal slices from CIE-exposed adolescent mice with a positive allosteric modulator of mGlu2 fully rescues mGlu2-LTD. In contrast to the 2-week CIE paradigm, acute exposure of striatal slices to ethanol concentrations that mimic ethanol levels during CIE exposure fails to disrupt mGlu2-LTD. We did not observe a reduction of mGlu2 mRNA or protein levels following CIE exposure, suggesting that alcohol effects on mGlu2 occur at the functional level. Our findings contribute to growing evidence that adolescents are uniquely vulnerable to certain alcohol-induced neuroadaptations, and identify enhancement of mGlu2 activity as a strategy to reverse the effects of adolescent alcohol exposure on DLS physiology.

Age-dependent impairment of metabotropic glutamate receptor 2-dependent long-term depression in the mouse striatum by chronic ethanol exposure. - Johnson, KA; Liput, DJ; Homanics, GE; Lovinger, DM (Alcohol, 2019)
Chronic alcohol exposure is associated with increased reliance on behavioral strategies involving the dorsolateral striatum (DLS), including habitual or stimulus-response behaviors. Presynaptic G protein-coupled receptors (GPCRs) on cortical and thalamic inputs to the DLS inhibit glutamate release, and alcohol-induced disruption of presynaptic GPCR function represents a mechanism by which alcohol could disinhibit DLS neurons and thus bias toward use of DLS-dependent behaviors. Metabotropic glutamate receptor 2 (mGlu2) is a Gi/o-coupled GPCR that robustly modulates glutamate transmission in the DLS, inducing long-term depression (LTD) at both cortical and thalamic synapses. Loss of mGlu2 function has recently been associated with increased ethanol seeking and consumption, but the ability of alcohol to produce adaptations in mGlu2 function in the DLS has not been investigated. We exposed male C57Bl/6J mice to a 2-week chronic intermittent ethanol (CIE) paradigm followed by a brief withdrawal period, then used whole-cell patch clamp recordings of glutamatergic transmission in the striatum to assess CIE effects on mGlu2-mediated synaptic plasticity. We report that CIE differentially disrupts mGlu2-mediated long-term depression in the DLS vs. dorsomedial striatum (DMS). Interestingly, CIE-induced impairment of mGlu2-LTD in the dorsolateral striatum is only observed when alcohol exposure occurs during adolescence. Incubation of striatal slices from CIE-exposed adolescent mice with a positive allosteric modulator of mGlu2 fully rescues mGlu2-LTD. In contrast to the 2-week CIE paradigm, acute exposure of striatal slices to ethanol concentrations that mimic ethanol levels during CIE exposure fails to disrupt mGlu2-LTD. We did not observe a reduction of mGlu2 mRNA or protein levels following CIE exposure, suggesting that alcohol effects on mGlu2 occur at the functional level. Our findings contribute to growing evidence that adolescents are uniquely vulnerable to certain alcohol-induced neuroadaptations, and identify enhancement of mGlu2 activity as a strategy to reverse the effects of adolescent alcohol exposure on DLS physiology.

Analysis of whole genome-transcriptomic organization in brain to identify genes associated with alcoholism - Kapoor M,; Wang JC,; Farris SP,; Liu Y,; McClintick J,; Gupta I,; Meyers JL,; Bertelsen S,; Chao M,; Nurnberger J,; Tischfield J,; Harari O,; et al. (Translational Psychiatry, 2019)
Alcohol exposure triggers changes in gene expression and biological pathways in human brain. We explored alterations in gene expression in the Pre-Frontal Cortex (PFC) of 65 alcoholics and 73 controls of European descent, and identified 129 genes that showed altered expression (FDR < 0.05) in subjects with alcohol dependence. Differentially expressed genes were enriched for pathways related to interferon signaling and Growth Arrest and DNA Damage-inducible 45 (GADD45) signaling. A coexpression module (thistle2) identified by weighted gene co-expression network analysis (WGCNA) was significantly correlated with alcohol dependence, alcohol consumption, and AUDIT scores. Genes in the thistle2 module were enriched with genes related to calcium signaling pathways and showed significant downregulation of these pathways, as well as enrichment for biological processes related to nicotine response and opioid signaling. A second module (brown4) showed significant upregulation of pathways related to immune signaling. Expression quantitative trait loci (eQTLs) for genes in the brown4 module were also enriched for genetic associations with alcohol dependence and alcohol consumption in large genome-wide studies included in the Psychiatric Genetic Consortium and the UK Biobank's alcohol consumption dataset. By leveraging multi-omics data, this transcriptome analysis has identified genes and biological pathways that could provide insight for identifying therapeutic targets for alcohol dependence.

Analysis of whole genome-transcriptomic organization in brain to identify genes associated with alcoholism - Kapoor M,; Farris SP,; Liu Y,; McClintick J,; Gupta I,; Meyers JL,; Bertelsen S,; Chao M,; Nurnberger J,; Tischfield J,; Harari O,; Zeran L,; et al. (Translational Psychiatry, 2019)
Alcohol exposure triggers changes in gene expression and biological pathways in human brain. We explored alterations in gene expression in the Pre-Frontal Cortex (PFC) of 65 alcoholics and 73 controls of European descent, and identified 129 genes that showed altered expression (FDR < 0.05) in subjects with alcohol dependence. Differentially expressed genes were enriched for pathways related to interferon signaling and Growth Arrest and DNA Damage-inducible 45 (GADD45) signaling. A coexpression module (thistle2) identified by weighted gene co-expression network analysis (WGCNA) was significantly correlated with alcohol dependence, alcohol consumption, and AUDIT scores. Genes in the thistle2 module were enriched with genes related to calcium signaling pathways and showed significant downregulation of these pathways, as well as enrichment for biological processes related to nicotine response and opioid signaling. A second module (brown4) showed significant upregulation of pathways related to immune signaling. Expression quantitative trait loci (eQTLs) for genes in the brown4 module were also enriched for genetic associations with alcohol dependence and alcohol consumption in large genome-wide studies included in the Psychiatric Genetic Consortium and the UK Biobank’s alcohol consumption dataset. By leveraging multi-omics data, this transcriptome analysis has identified genes and biological pathways that could provide insight for identifying therapeutic targets for alcohol dependence.

Brain-behavior relations and effects of aging and common comorbidities in alcohol use disorder: a review. - Sullivan, EV; Pfefferbaum, A (Neuropsychology, 2019)
OBJECTIVE: Alcohol use disorder (AUD) is a complex, dynamic condition that waxes and wanes with unhealthy drinking episodes and varies in drinking patterns and effects on brain structure and function with age. Its excessive use renders chronically heavy drinkers vulnerable to direct alcohol toxicity and a variety of comorbidities attributable to nonalcohol drug misuse, viral infections, and accelerated or premature aging. AUD affects widespread brain systems, commonly, frontolimbic, frontostriatal, and frontocerebellar networks. METHOD AND RESULTS: Multimodal assessment using selective neuropsychological testing and whole-brain neuroimaging provides evidence for AUD-related specific brain structure-function relations established with double dissociations. Longitudinal study using noninvasive imaging provides evidence for brain structural and functional improvement with sustained sobriety and further decline with relapse. Functional imaging suggests the possibility that some alcoholics in recovery can compensate for impairment by invoking brain systems typically not used for a target task but that can enable normal-level performance. CONCLUSIONS: Evidence for AUD-aging interactions, indicative of accelerated aging, together with increasing alcohol consumption in middle-age and older adults, put aging drinkers at special risk for developing cognitive decline and possibly dementia. (PsycINFO Database Record (c) 2019 APA, all rights reserved).

Brain-behavior relations and effects of aging and common comorbidities in alcohol use disorder: A review - Sullivan EV; Pfefferbaum A, (Neuropsychology, 2019)
Objective: Alcohol use disorder (AUD) is a complex, dynamic condition that waxes and wanes with unhealthy drinking episodes and varies in drinking patterns and effects on brain structure and function with age. Its excessive use renders chronically heavy drinkers vulnerable to direct alcohol toxicity and a variety of comorbidities attributable to nonalcohol drug misuse, viral infections, and accelerated or premature aging. AUD affects widespread brain systems, commonly, frontolimbic, frontostriatal, and frontocerebellar networks. Method and Results: Multimodal assessment using selective neuropsychological testing and whole-brain neuroimaging provides evidence for AUD-related specific brain structure-function relations established with double dissociations. Longitudinal study using noninvasive imaging provides evidence for brain structural and functional improvement with sustained sobriety and further decline with relapse. Functional imaging suggests the possibility that some alcoholics in recovery can compensate for impairment by invoking brain systems typically not used for a target task but that can enable normal-level performance. Conclusions: Evidence for AUD-aging interactions, indicative of accelerated aging, together with increasing alcohol consumption in middle-age and older adults, put aging drinkers at special risk for developing cognitive decline and possibly dementia. (PsycINFO Database Record (c) 2019 APA, all rights reserved)

Cannabis and Alcohol: From Basic Science to Public Policy - Chung T,; Harris RA (Alcoholism: Clinical and Experimental Research, 2019)
The emergence of state‐level approval of cannabis for both medical and recreational use is likely to increase the already prevalent co‐use of alcohol and cannabis (Yurasek et al., 2017) and raise many important health and social concerns (National Academies of Sciences, 2017). Cannabis research has lagged behind that of alcohol research, but important studies are emerging on the interactions between alcohol and cannabinoids. In this Virtual Issue, Cannabis and Alcohol: From Basic Science to Public Policy, we present 9 leading‐edge research publications spanning preclinical and epidemiological studies, as well as a critical review of the potential therapeutic use of cannabidiol (CBD) in the treatment of alcohol use disorder (AUD) (Turna et al., 2019), which recently appeared in Alcoholism: Clinical and Experimental Research. The Virtual Issue addresses the potential risks and benefits of alcohol and cannabis co‐use, which may depend on the particular subgroup of individuals, and whether these drugs are used simultaneously (i.e., drug effects overlap) (Pakula et al., 2009) or concurrently (i.e., drug effects do not overlap in time) (Subbaraman et al., 2019). Simultaneous drug use may be perceived as a means to complement or enhance the effects of each substance (Patrick et al., 2018), despite some individuals reporting negative effects (Lee et al., 2017). The positive perception of complementary drug effects is concerning given the greater health risks associated with simultaneous use (Volkow et al., 2014; Yurasek et al., 2017). Another pattern of use has also developed that substitutes cannabis for alcohol use, particularly in individuals who are making efforts to reduce alcohol intake (Subbaraman, 2016). As summarized in the sections below, this Virtual Issue provides a current assessment of cannabis–alcohol interactions and shows patterns of drug use and risk profiles that may impact the prevalence of co‐use and dependence.

Cannabis and alcohol: from basic science to public policy. - Chung, T; Harris, R A (Alcoholism: Clinical and Experimental Research, 2019)
The emergence of state-level approval of cannabis for both medical and recreational use is likely to increase the already prevalent co-use of alcohol and cannabis (Yurasek et al., 2017) and raise many important health and social concerns (National Academies of Sciences, 2017). Cannabis research has lagged behind that of alcohol research, but important studies are emerging on the interactions between alcohol and cannabinoids. In this Virtual Issue, Cannabis and Alcohol: From Basic Science to Public Policy, we present 9 leading-edge research publications spanning preclinical and epidemiological studies, as well as a critical review of the potential therapeutic use of cannabidiol (CBD) in the treatment of alcohol use disorder (AUD) (Turna et al., 2019), which recently appeared in Alcoholism: Clinical and Experimental Research. The Virtual Issue addresses the potential risks and benefits of alcohol and cannabis co-use, which may depend on the particular subgroup of individuals, and whether these drugs are used simultaneously (i.e., drug effects overlap) (Pakula et al., 2009) or concurrently (i.e., drug effects do not overlap in time) (Subbaraman et al., 2019). Simultaneous drug use may be perceived as a means to complement or enhance the effects of each substance (Patrick et al., 2018), despite some individuals reporting negative effects (Lee et al., 2017). The positive perception of complementary drug effects is concerning given the greater health risks associated with simultaneous use (Volkow et al., 2014; Yurasek et al., 2017). Another pattern of use has also developed that substitutes cannabis for alcohol use, particularly in individuals who are making efforts to reduce alcohol intake (Subbaraman, 2016). As summarized in the sections below, this Virtual Issue provides a current assessment of cannabis–alcohol interactions and shows patterns of drug use and risk profiles that may impact the prevalence of co-use and dependence.

Central Nervous System Correlates of “Objective” Neuropathy in Alcohol Use Disorder - Zahr NM; Pohl KM; Pfefferbaum A,; Sullivan EV (Alcoholism: Clinical and Experimental Research, 2019)
Background Among the neurological consequences of alcoholism is peripheral neuropathy. Relative to human immunodeficiency virus (HIV) or diabetes‐related neuropathies, neuropathy associated with alcohol use disorders (AUD ) is understudied. In both the diabetes and HIV literature, emerging evidence supports a central nervous system (CNS) component to peripheral neuropathy. Methods In seeking a central substrate for AUD ‐related neuropathy, the current study was conducted in 154 individuals with AUD (43 women, age 21 to 74 years) and 99 healthy controls (41 women, age 21 to 77 years) and explored subjective symptoms (self‐report) and objective signs (perception of vibration, deep tendon ankle reflex, position sense, 2‐point discrimination) of neuropathy separately. In addition to regional brain volumes, risk factors for AUD ‐related neuropathy, including age, sex, total lifetime ethanol consumed, nutritional indices (i.e., thiamine, folate), and measures of liver integrity (i.e., γ ‐glutamyltransferase), were evaluated. Results The AUD group described more subjective symptoms of neuropathy and was more frequently impaired on bilateral perception of vibration. From 5 correlates, the number of AUD ‐related seizures was most significantly associated with subjective symptoms of neuropathy. There were 15 correlates of impaired perception of vibration among the AUD participants: Of these, age and volume of frontal precentral cortex were the most robust predictors. Conclusions This study supports CNS involvement in objective signs of neuropathy in AUD.

Central nervous system correlates of "objective" neuropathy in alcohol use disorder. - Zahr, NM; Pohl, KM; Pfefferbaum, A; Sullivan, EV (Alcoholism: Clinical and Experimental Research, 2019)
BACKGROUND: Among the neurological consequences of alcoholism is peripheral neuropathy. Relative to human immunodeficiency virus (HIV) or diabetes-related neuropathies, neuropathy associated with alcohol use disorders (AUD) is understudied. In both the diabetes and HIV literature, emerging evidence supports a central nervous system (CNS) component to peripheral neuropathy. METHODS: In seeking a central substrate for AUD-related neuropathy, the current study was conducted in 154 individuals with AUD (43 women, age 21 to 74 years) and 99 healthy controls (41 women, age 21 to 77 years) and explored subjective symptoms (self-report) and objective signs (perception of vibration, deep tendon ankle reflex, position sense, 2-point discrimination) of neuropathy separately. In addition to regional brain volumes, risk factors for AUD-related neuropathy, including age, sex, total lifetime ethanol consumed, nutritional indices (i.e., thiamine, folate), and measures of liver integrity (i.e., γ-glutamyltransferase), were evaluated. RESULTS: The AUD group described more subjective symptoms of neuropathy and was more frequently impaired on bilateral perception of vibration. From 5 correlates, the number of AUD-related seizures was most significantly associated with subjective symptoms of neuropathy. There were 15 correlates of impaired perception of vibration among the AUD participants: Of these, age and volume of frontal precentral cortex were the most robust predictors. CONCLUSIONS: This study supports CNS involvement in objective signs of neuropathy in AUD.

Conditioned stimuli affect ethanol-seeking by female alcohol-preferring (P) rats: the role of repeated-deprivations, cue-pretreatment, and cue-temporal intervals. - Hauser, SR; Deehan, GA Jr; Knight, CP; Waeiss, RA; Truitt, WA; Johnson, PL; Bell, RL; McBride, WJ; Rodd, ZA (Psychopharmacology, 2019)
RATIONALE: Evidence indicates that drug-paired stimuli can evoke drug-craving leading to drug-seeking and repeated relapse periods can influence drug-seeking behaviors. OBJECTIVES: The present study examined (1) the effect of an interaction between repeated deprivation cycles and excitatory conditioning stimuli (CS+) on ethanol (EtOH)-seeking; (2) the effects of EtOH-paired cue-exposure in a non-drug-paired environment on subsequent conditioning in a drug-paired environment; and (3) the temporal effects of conditioned cues on subsequent EtOH-seeking. METHODS: Adult female alcohol-preferring (P) rats were exposed to three conditioned odor cues; CS+ associated with EtOH self-administration, CS- associated with the absence of EtOH (extinction training), and a neutral stimulus (CS0) presented in a neutral non-drug-paired environment. The rats underwent four deprivation cycles or were non-deprived, following extinction they were maintained in a home cage for an EtOH-free period, and then exposed to no cue, CS+, CS-, or CS0 to assess the effect of the conditioned cues on EtOH-seeking behavior. RESULTS: Repeated deprivations enhanced and prolonged the duration of CS+ effects on EtOH-seeking. Presentation of the CS- in a non-drug-paired environment blocked the ability of a CS+ to enhance EtOH-seeking in a drug-paired environment. Presentation of the CS+ or CS- in a non-drug-paired environment 2 or 4 h earlier significantly altered EtOH-seeking. CONCLUSION: Results indicated an interaction between repeated deprivation cycles and CS+ resulted in a potentiation of CS+ evoked EtOH-seeking. In addition, a CS- may have therapeutic potential by providing prophylactic protection against relapse behavior in the presence of cues in the drug-using environment.

Conditioned stimuli affect ethanol-seeking by female alcohol-preferring (P) rats: the role of repeated-deprivations, cue-pretreatment, and cue-temporal intervals - Hauser SR,; Deehan GA Jr,; Knight CP,; Waeiss RA,; Truitt WA,; Johnson PL,; Bell RL,; McBride WJ,; Rodd ZA (Psychopharmacology, 2019)
Rationale Evidence indicates that drug-paired stimuli can evoke drug-craving leading to drug-seeking and repeated relapse periods can influence drug-seeking behaviors. Objectives The present study examined (1) the effect of an interaction between repeated deprivation cycles and excitatory conditioning stimuli (CS+) on ethanol (EtOH)-seeking; (2) the effects of EtOH-paired cue-exposure in a non-drug-paired environment on subsequent conditioning in a drug-paired environment; and (3) the temporal effects of conditioned cues on subsequent EtOH-seeking. Methods Adult female alcohol-preferring (P) rats were exposed to three conditioned odor cues; CS+ associated with EtOH self-administration, CS− associated with the absence of EtOH (extinction training), and a neutral stimulus (CS0) presented in a neutral non-drug-paired environment. The rats underwent four deprivation cycles or were non-deprived, following extinction they were maintained in a home cage for an EtOH-free period, and then exposed to no cue, CS+, CS−, or CS0 to assess the effect of the conditioned cues on EtOH-seeking behavior. Results   Repeated deprivations enhanced and prolonged the duration of CS+ effects on EtOH-seeking. Presentation of the CS− in a non-drug-paired environment blocked the ability of a CS+ to enhance EtOH-seeking in a drug-paired environment. Presentation of the CS+ or CS− in a non-drug-paired environment 2 or 4 h earlier significantly altered EtOH-seeking. Conclusion Results indicated an interaction between repeated deprivation cycles and CS+ resulted in a potentiation of CS+ evoked EtOH-seeking. In addition, a CS− may have therapeutic potential by providing prophylactic protection against relapse behavior in the presence of cues in the drug-using environment.

Control of aversion by glycine-gated GluN1/GluN3A NMDA receptors in the adult medial habenula. - Otsu, Y; Darcq, E; Pietrajtis, K; Mátyás, F; Schwartz, E; Bessaih, T; Abi Gerges, S; Rousseau, CV; Grand, T; Dieudonné, S; Paoletti, P; Acsády, L; et al. (Science, 2019)
The unconventional N-methyl-D-aspartate (NMDA) receptor subunits GluN3A and GluN3B can, when associated with the other glycine-binding subunit GluN1, generate excitatory conductances purely activated by glycine. However, functional GluN1/GluN3 receptors have not been identified in native adult tissues. We discovered that GluN1/GluN3A receptors are operational in neurons of the mouse adult medial habenula (MHb), an epithalamic area controlling aversive physiological states. In the absence of glycinergic neuronal specializations in the MHb, glial cells tuned neuronal activity via GluN1/GluN3A receptors. Reducing GluN1/GluN3A receptor levels in the MHb prevented place-aversion conditioning. Our study extends the physiological and behavioral implications of glycine by demonstrating its control of negatively valued emotional associations via excitatory glycinergic NMDA receptors.

Control of aversion by glycine-gated GluN1/GluN3A NMDA receptors in the adult medial habenula - Otsu Y,; Darcq E,; Pietrajtis K,; Mátyás F,; Schwartz E,; Bessaih T,; Abi Gerges S,; Rousseau CV,; Grand T,; Dieudonné S,; Paoletti P,; Acsády L,; et al. (Science, 2019)
The unconventional N-methyl-D-aspartate (NMDA) receptor subunits GluN3A and GluN3B can, when associated with the other glycine-binding subunit GluN1, generate excitatory conductances purely activated by glycine. However, functional GluN1/GluN3 receptors have not been identified in native adult tissues. We discovered that GluN1/GluN3A receptors are operational in neurons of the mouse adult medial habenula (MHb), an epithalamic area controlling aversive physiological states. In the absence of glycinergic neuronal specializations in the MHb, glial cells tuned neuronal activity via GluN1/GluN3A receptors. Reducing GluN1/GluN3A receptor levels in the MHb prevented place-aversion conditioning. Our study extends the physiological and behavioral implications of glycine by demonstrating its control of negatively valued emotional associations via excitatory glycinergic NMDA receptors.

Convergence of three parcellation approaches demonstrating cerebellar lobule volume deficits in Alcohol Use Disorder. - Sullivan, EV; Zahr, NM; Saranathan, M; Pohl, KM; Pfefferbaum, A (Neuroimage: Clinical, 2019)
Recent advances in robust and reliable methods of MRI-derived cerebellar lobule parcellation volumetry present the opportunity to assess effects of Alcohol Use Disorder (AUD) on selective cerebellar lobules and relations with indices of nutrition and motor functions. In pursuit of this opportunity, we analyzed high-resolution MRI data acquired in 24 individuals with AUD and 20 age- and sex-matched controls with a 32-channel head coil using three different atlases: the online automated analysis pipeline volBrain Ceres, SUIT, and the Johns Hopkins atlas. Participants had also completed gait and balance examination and hematological analysis of nutritional and liver status, enabling testing of functional meaningfulness of each cerebellar parcellation scheme. Compared with controls, each quantification approach yielded similar patterns of group differences in regional volumes: All three approaches identified AUD-related deficits in total tissue and total gray matter, but only Ceres identified a total white matter volume deficit. Convergent volume differences occurred in lobules I-V, Crus I, VIIIB, and IX. Coefficients of variation (CVs) were <20% for 46 of 56 regions measured and in general were graded: Ceres<SUIT<Hopkins. The most robust correlations were identified between poorer stability in balancing on one leg and smaller lobule VI and Crus I volumes from the Ceres atlas. Lower values of two essential vitamins-thiamine (vitamin B1) and serum folate (vitamin B9)-along with lower red blood cell count, which are dependent on adequate levels of B vitamins, correlated with smaller gray matter volumes of lobule VI and Crus I. Higher γ-glutamyl transferase (GGT) levels, possibly reflecting compromised liver function, correlated with smaller volumes of lobules VI and X. These initial results based on high resolution data produced with clinically practical imaging procedures hold promise for expanding our knowledge about the relevance of focal cerebellar morphology in AUD and other neuropsychiatric conditions.

Convergence of three parcellation approaches demonstrating cerebellar lobule volume deficits in Alcohol Use Disorder - Sullivan EV; Zahr NM; Saranathan M; Pohl KM; Pfefferbaum A, (Neuroimage: Clinical, 2019)
Recent advances in robust and reliable methods of MRI-derived cerebellar lobule parcellation volumetry present the opportunity to assess effects of Alcohol Use Disorder (AUD) on selective cerebellar lobules and relations with indices of nutrition and motor functions. In pursuit of this opportunity, we analyzed high-resolution MRI data acquired in 24 individuals with AUD and 20 age- and sex-matched controls with a 32-channel head coil using three different atlases: the online automated analysis pipeline volBrain Ceres, SUIT, and the Johns Hopkins atlas. Participants had also completed gait and balance examination and hematological analysis of nutritional and liver status, enabling testing of functional meaningfulness of each cerebellar parcellation scheme. Compared with controls, each quantification approach yielded similar patterns of group differences in regional volumes: All three approaches identified AUD-related deficits in total tissue and total gray matter, but only Ceres identified a total white matter volume deficit. Convergent volume differences occurred in lobules I-V, Crus I, VIIIB, and IX. Coefficients of variation (CVs) were <20% for 46 of 56 regions measured and in general were graded: Ceres<SUIT<Hopkins. The most robust correlations were identified between poorer stability in balancing on one leg and smaller lobule VI and Crus I volumes from the Ceres atlas. Lower values of two essential vitamins—thiamine (vitamin B1) and serum folate (vitamin B9)—along with lower red blood cell count, which are dependent on adequate levels of B vitamins, correlated with smaller gray matter volumes of lobule VI and Crus I. Higher γ-glutamyl transferase (GGT) levels, possibly reflecting compromised liver function, correlated with smaller volumes of lobules VI and X. These initial results based on high resolution data produced with clinically practical imaging procedures hold promise for expanding our knowledge about the relevance of focal cerebellar morphology in AUD and other neuropsychiatric conditions.

Dissecting Brain Networks Underlying Alcohol Binge Drinking Using a Systems Genomics Approach - Ferguson LB,; Zhang L,; Kircher D,; Wang S,; Mayfield RD; Crabbe JC,; Morrisett RA; Harris RA; Ponomarev I, (Molecular Neurobiology, 2019)
Alcohol use disorder (AUD) is a complex psychiatric disorder with strong genetic and environmental risk factors. We studied the molecular perturbations underlying risky drinking behavior by measuring transcriptome changes across the neurocircuitry of addiction in a genetic mouse model of binge drinking. Sixteen generations of selective breeding for high blood alcohol levels after a binge drinking session produced global changes in brain gene expression in alcohol-naïve High Drinking in the Dark (HDID-1) mice. Using gene expression profiles to generate circuit-level hypotheses, we developed a systems approach that integrated regulation of gene coexpression networks across multiple brain regions, neuron-specific transcriptional signatures, and knowledgebase analytics. Whole-cell, voltage-clamp recordings from nucleus accumbens shell neurons projecting to the ventral tegmental area showed differential ethanol-induced plasticity in HDID-1 and control mice and provided support for one of the hypotheses. There were similarities in gene networks between HDID-1 mouse brains and postmortem brains of human alcoholics, suggesting that some gene expression patterns associated with high alcohol consumption are conserved across species. This study demonstrated the value of gene networks for data integration across biological modalities and species to study mechanisms of disease.

Dissecting brain networks underlying alcohol binge drinking using a systems genomics approach. - Ferguson, LB; Zhang, L; Kircher, D; Wang S,; Mayfield, R D; Crabbe, JC; Morrisett, RA; Harris, R A; Ponomarev, I. (Molecular Neurobiology, 2019)
Alcohol use disorder (AUD) is a complex psychiatric disorder with strong genetic and environmental risk factors. We studied the molecular perturbations underlying risky drinking behavior by measuring transcriptome changes across the neurocircuitry of addiction in a genetic mouse model of binge drinking. Sixteen generations of selective breeding for high blood alcohol levels after a binge drinking session produced global changes in brain gene expression in alcohol-naïve High Drinking in the Dark (HDID-1) mice. Using gene expression profiles to generate circuit-level hypotheses, we developed a systems approach that integrated regulation of gene coexpression networks across multiple brain regions, neuron-specific transcriptional signatures, and knowledgebase analytics. Whole-cell, voltage-clamp recordings from nucleus accumbens shell neurons projecting to the ventral tegmental area showed differential ethanol-induced plasticity in HDID-1 and control mice and provided support for one of the hypotheses. There were similarities in gene networks between HDID-1 mouse brains and postmortem brains of human alcoholics, suggesting that some gene expression patterns associated with high alcohol consumption are conserved across species. This study demonstrated the value of gene networks for data integration across biological modalities and species to study mechanisms of disease.

Ethanol acts on KCNK13 potassium channels in the ventral tegmental area to increase firing rate and modulate binge–like drinking - You C,; Savarese A,; Vandegrift BJ,; He D,; Pandey SC,; Lasek AW,; Brodie MS, (Neuropharmacology, 2019)
Alcohol excitation of the ventral tegmental area (VTA) is important in neurobiological processes related to the development of alcoholism. The ionotropic receptors on VTA neurons that mediate ethanol-induced excitation have not been identified. Quinidine blocks ethanol excitation of VTA neurons, and blockade of two-pore potassium channels is among the actions of quinidine. Therefore two-pore potassium channels in the VTA may be potential targets for the action of ethanol. Here, we explored whether ethanol activation of VTA neurons is mediated by the two-pore potassium channel KCNK13. Extracellular recordings of the response of VTA neurons to ethanol were performed in combination with knockdown of Kcnk13 using a short hairpin RNA (shRNA) in C57BL/6 J mice. Real-time PCR and immunohistochemistry were used to examine expression of this channel in the VTA. Finally, the role of KCNK13 in binge-like drinking was examined in the drinking in the dark test after knockdown of the channel. Kcnk13 expression in the VTA was increased by acute ethanol exposure. Ethanol-induced excitation of VTA neurons was selectively reduced by shRNA targeting Kcnk13. Importantly, knockdown of Kcnk13 in the VTA resulted in increased alcohol drinking. These results are consistent with the idea that ethanol stimulates VTA neurons at least in part by inhibiting KCNK13, a specific two-pore potassium channel, and that KCNK13 can control both VTA neuronal activity and binge drinking. KCNK13 is a novel alcohol-sensitive molecular target and may be amenable to the development of pharmacotherapies for alcoholism treatment.

Ethanol acts on KCNK13 potassium channels in the ventral tegmental area to increase firing rate and modulate binge-like drinking - You, C; Savarese, A; Vandegrift, BJ; He, D; Pandey, SC; Lasek, AW; Brodie, MS (Neuropharmacology, 2019)
Alcohol excitation of the ventral tegmental area (VTA) is important in neurobiological processes related to the development of alcoholism. The ionotropic receptors on VTA neurons that mediate ethanol-induced excitation have not been identified. Quinidine blocks ethanol excitation of VTA neurons, and blockade of two-pore potassium channels is among the actions of quinidine. Therefore two-pore potassium channels in the VTA may be potential targets for the action of ethanol. Here, we explored whether ethanol activation of VTA neurons is mediated by the two-pore potassium channel KCNK13. Extracellular recordings of the response of VTA neurons to ethanol were performed in combination with knockdown of Kcnk13 using a short hairpin RNA (shRNA) in C57BL/6 J mice. Real-time PCR and immunohistochemistry were used to examine expression of this channel in the VTA. Finally, the role of KCNK13 in binge-like drinking was examined in the drinking in the dark test after knockdown of the channel. Kcnk13 expression in the VTA was increased by acute ethanol exposure. Ethanol-induced excitation of VTA neurons was selectively reduced by shRNA targeting Kcnk13. Importantly, knockdown of Kcnk13 in the VTA resulted in increased alcohol drinking. These results are consistent with the idea that ethanol stimulates VTA neurons at least in part by inhibiting KCNK13, a specific two-pore potassium channel, and that KCNK13 can control both VTA neuronal activity and binge drinking. KCNK13 is a novel alcohol-sensitive molecular target and may be amenable to the development of pharmacotherapies for alcoholism treatment.

Ethanol and a rapid-acting antidepressant produce overlapping changes in exon expression in the synaptic transcriptome. - Wolfe SA,; Farris SP,; Mayfield JE,; Heaney CF,; Erickson EK,; Harris, R A; Mayfield, R D; Raab-Graham, KF (Neuropharmacology, 2019)
Alcohol use disorder (AUD) and major depressive disorder (MDD) are prevalent, debilitating, and highly comorbid disorders. The molecular changes that underlie their comorbidity are beginning to emerge. For example, recent evidence showed that acute ethanol exposure produces rapid antidepressant-like biochemical and behavioral responses. Both ethanol and fast-acting antidepressants block N-methyl-D-aspartate receptor (NMDAR) activity, leading to synaptic changes and long-lasting antidepressant-like behavioral effects. We used RNA sequencing to analyze changes in the synaptic transcriptome after acute treatment with ethanol or the NMDAR antagonist, Ro 25-6981. Ethanol and Ro 25-6981 induced differential, independent changes in gene expression. In contrast with gene-level expression, ethanol and Ro 25-6981 produced overlapping changes in exons, as measured by analysis of differentially expressed exons (DEEs). A prominent overlap in genes with DEEs indicated that changes in exon usage were important for both ethanol and Ro 25-6981 action. Structural modeling provided evidence that ethanol-induced exon expression in the NMDAR1 amino-terminal domain could induce conformational changes and thus alter NMDAR function. These findings suggest that the rapid antidepressant effects of ethanol and NMDAR antagonists reported previously may depend on synaptic exon usage rather than gene expression.

Ethanol Conditioned Taste Aversion in High Drinking in the Dark Mice - Crabbe JC,; Metten P,; Savarese AM,; Ozburn AR,; Schlumbohm JP,; Spence SE,; Hack WR, (Brain Sciences, 2019)
Two independent lines of High Drinking in the Dark (HDID-1, HDID-2) mice have been bred to reach high blood alcohol levels after a short period of binge-like ethanol drinking. Male mice of both lines were shown to have reduced sensitivity to develop a taste aversion to a novel flavor conditioned by ethanol injections as compared with their unselected HS/NPT founder stock. We have subsequently developed inbred variants of each line. The current experiments established that reduced ethanol-conditioned taste aversion is also seen in the inbred variants, in both males and females. In other experiments, we asked whether HDID mice would ingest sufficient doses of ethanol to lead to a conditioned taste aversion upon retest. Different manipulations were used to elevate consumption of ethanol on initial exposure. Access to increased ethanol concentrations, to multiple tubes of ethanol, and fluid restriction to increase thirst motivation all enhanced initial drinking of ethanol. Each condition led to reduced intake the next day, consistent with a mild conditioned taste aversion. These experiments support the conclusion that one reason contributing to the willingness of HDID mice to drink to the point of intoxication is a genetic insensitivity to the aversive effects of ethanol.

Ethanol conditioned taste aversion in high drinking in the dark mice - Crabbe JC,; Metten P,; Savarese AM,; Ozburn AR,; Schlumbohm JP,; Spence SE,; Hack WR, (Brain Sciences, 2019)
Two independent lines of High Drinking in the Dark (HDID-1, HDID-2) mice have been bred to reach high blood alcohol levels after a short period of binge-like ethanol drinking. Male mice of both lines were shown to have reduced sensitivity to develop a taste aversion to a novel flavor conditioned by ethanol injections as compared with their unselected HS/NPT founder stock. We have subsequently developed inbred variants of each line. The current experiments established that reduced ethanol-conditioned taste aversion is also seen in the inbred variants, in both males and females. In other experiments, we asked whether HDID mice would ingest sufficient doses of ethanol to lead to a conditioned taste aversion upon retest. Different manipulations were used to elevate consumption of ethanol on initial exposure. Access to increased ethanol concentrations, to multiple tubes of ethanol, and fluid restriction to increase thirst motivation all enhanced initial drinking of ethanol. Each condition led to reduced intake the next day, consistent with a mild conditioned taste aversion. These experiments support the conclusion that one reason contributing to the willingness of HDID mice to drink to the point of intoxication is a genetic insensitivity to the aversive effects of ethanol.

Ethanol Experience Enhances Glutamatergic Ventral Hippocampal Inputs to D1 Receptor-Expressing Medium Spiny Neurons in the Nucleus Accumbens Shell - Kircher DM,; Aziz HC,; Mangieri RA; Morrisett RA (Journal of Neuroscience, 2019)
A growing number of studies implicate alterations in glutamatergic signaling within the reward circuitry of the brain during alcohol abuse and dependence. A key integrator of glutamatergic signaling in the reward circuit is the nucleus accumbens, more specifically, the dopamine D1 receptor-expressing medium spiny neurons (D1-MSNs) within this region, which have been implicated in the formation of dependence to many drugs of abuse including alcohol. D1-MSNs receive glutamatergic input from several brain regions; however, it is not currently known how individual inputs onto D1-MSNs are altered by alcohol experience. Here, we investigate input-specific adaptations in glutamatergic transmission in response to varying levels of alcohol experience. Virally mediated expression of Channelrhodopsin in ventral hippocampal (vHipp) glutamate neurons of male mice allowed for selective activation of vHipp to D1-MSN synapses. Therefore, we were able to compare synaptic adaptations in response to low and high alcohol experience in vitro and in vivo. Alcohol experience enhanced glutamatergic activity and abolished LTD at vHipp to D1-MSN synapses. Following chronic alcohol experience, GluA2-lacking AMPARs, which are Ca permeable, were inserted into vHipp to D1-MSN synapses. These findings support the reversal of alcohol-induced insertion of Ca-permeable AMPARs and the enhancement of glutamatergic activity at vHipp to D1-MSNs as potential targets for intervention during early exposure to alcohol.

Ethanol experience enhances glutamatergic ventral hippocampal inputs to D1 receptor-expressing medium spiny neurons in the nucleus accumbens shell - Kircher DM,; Aziz H,; Mangieri R,; Morrisett R (The Journal of neuroscience, 2019)
Nucleus accumbens dopamine D1 receptor-expressing medium spiny neurons (D1-MSNs) have been implicated in the formation of dependence to many drugs of abuse including alcohol. Previous studies have revealed that acute alcohol exposure suppresses glutamatergic signaling within the accumbens and repeated alcohol exposure enhances glutamatergic signaling. D1-MSNs receive glutamatergic input from several brain regions and it is not currently known how individual inputs onto D1-MSNs are altered by alcohol experience. To Address this, we used virally mediated expression of Channelrhodopsin (ChR2) in ventral hippocampal (vHipp) glutamate neurons to selectively activate vHipp to D1-MSN synapses and compared synaptic adaptations in response to low and high alcohol experience in vitro and in vivo. Alcohol experience enhanced glutamatergic activity and abolished long-term depression (LTD) at ventral hippocampal (vHipp) to D1-MSN synapses. Following chronic alcohol experience GluA2-lacking AMPA receptors, which are Ca-permeable, were inserted into vHipp to D1-MSN synapses. These alcohol-induced adaptations of glutamatergic signaling occurred at lower levels of exposure than previously reported. The loss of LTD expression and enhancement in glutamatergic signaling from the vHipp to D1-MSNs in the nucleus accumbens may play a critical role in the formation of alcohol dependence and enhancements in ethanol consumption. Reversal of alcohol-induced insertion of Ca-permeable AMPA receptors and enhancement of glutamatergic activity at vHipp to D1-MSNs presents potential targets for intervention during early exposure to alcohol. SIGNIFICANCE STATEMENT The work presented here is the first to elucidate how an individual glutamatergic input onto D1-MSNs of the accumbens shell (shNAc) are altered by repeated ethanol exposure. Our findings suggest that glutamatergic input from the ventral hippocampus (vHipp) onto D1-MSNs is enhanced following drinking in a two-bottle choice (2BC) paradigm and is further enhanced by chronic intermittent ethanol (CIE) vapor exposure which escalated volitional ethanol intake. A critical finding was the insertion of Ca-permeable AMPA receptors into vHipp-shNAc D1-MSN synapses following CIE exposure, and more importantly following ethanol consumption in the absence of vapor exposure. These findings suggest that enhancements of glutamatergic input from the vHipp and insertion of Ca-permeable AMPARs play a role in the formation of ethanol dependence.

Ethanol experience enhances glutamatergic ventral hippocampal inputs to D1 receptor-expressing medium spiny neurons in the nucleus accumbens shell. - Kircher, DM; Aziz, HC; Mangieri, RA; Morrisett, RA (Journal of Neuroscience, 2019)
A growing number of studies implicate alterations in glutamatergic signaling within the reward circuitry of the brain during alcohol abuse and dependence. A key integrator of glutamatergic signaling in the reward circuit is the nucleus accumbens, more specifically, the dopamine D1 receptor-expressing medium spiny neurons (D1-MSNs) within this region, which have been implicated in the formation of dependence to many drugs of abuse including alcohol. D1-MSNs receive glutamatergicinput from several brain regions; however, it is not currently known how individual inputs onto D1-MSNs are altered by alcohol experience. Here, we investigate input-specific adaptations in glutamatergic transmission in response to varying levels of alcohol experience. Virally mediated expression of Channelrhodopsin in ventral hippocampal (vHipp) glutamate neurons of male mice allowed for selective activation of vHipp to D1-MSN synapses. Therefore, we were able to compare synaptic adaptations in response to low and high alcohol experience in vitro and in vivo Alcohol experience enhanced glutamatergic activity and abolished LTD at vHipp to D1-MSN synapses. Following chronic alcohol experience, GluA2-lacking AMPARs, which are Ca permeable, were inserted into vHipp to D1-MSN synapses. These findings support the reversal of alcohol-induced insertion of Ca-permeable AMPARs and the enhancement of glutamatergic activity at vHipp to D1-MSNs as potential targets for intervention during early exposure to alcohol. SIGNIFICANCE STATEMENT Given the roles of the nucleus accumbens (NAc) in integrating cortical and allocortical information and in reward learning, it is vital to understand how inputs to this region are altered by drugs of abuse such as alcohol. The strength of excitatory inputs from the ventral hippocampus (vHipp) to the NAc has been positively associated with reward-related behaviors, but it is unclear whether or how ethanol affects these inputs. Here we show that vHipp-NAc synapses indeed are altered by ethanolexposure, with vHipp glutamatergic input to the NAc being enhanced following chronic ethanol experience. This work provides insight into ethanol-induced alterations of vHipp-NAc synapses and suggests that, similarly to drugs such as cocaine, the strengthening of these synapses promotes reward behavior.

Gene-edited CRISPy Critters for alcohol research - Homanics GE, (Alcohol, 2019)
Genetically engineered animals are powerful tools that have provided invaluable insights into mechanisms of alcohol action and alcohol-use disorder. Traditionally, production of gene-targeted animals was a tremendously expensive, time consuming, and technically demanding undertaking. However, the recent advent of facile methods for editing the genome at very high efficiency is revolutionizing how these animals are made. While pioneering approaches to create gene-edited animals first used zinc finger nucleases and subsequently used <a href="https://www.sciencedirect.com/topics/medicine-and-dentistry/transcription-activator-like-effector-nuclease" title="Learn more about Transcription Activator Like Effector Nuclease from ScienceDirect's AI-generated Topic Pages">transcription activator-like effector nucleases, these approaches have been largely supplanted in an extremely short period of time with the recent discovery and precocious maturation of the <a href="https://www.sciencedirect.com/topics/medicine-and-dentistry/clustered-regularly-interspaced-short-palindromic-repeat" title="Learn more about Clustered Regularly Interspaced Short Palindromic Repeat from ScienceDirect's AI-generated Topic Pages">Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) system. <a href="https://www.sciencedirect.com/topics/medicine-and-dentistry/clustered-regularly-interspaced-short-palindromic-repeat" title="Learn more about Clustered Regularly Interspaced Short Palindromic Repeat from ScienceDirect's AI-generated Topic Pages">CRISPR uses a short RNA sequence to guide a non-specific CRISPR-associated nuclease (Cas) to a precise, single location in the genome. Because the CRISPR/Cas system can be cheaply, rapidly, and easily reprogrammed to target nearly any genomic locus of interest simply by recoding the sequence of the guide RNA, this gene-editing system has been rapidly adopted by numerous labs around the world. With CRISPR/Cas, it is now possible to perform gene editing directly in early embryos from every species of animals that is of interest to the alcohol field. Techniques have been developed that enable the rapid production of animals in which a gene has been inactivated (knockout) or modified to harbor specific nucleotide changes (knockins). This system has also been used to insert specific DNA sequences such as reporter or recombinase genes into specific loci of interest. Genetically engineered animals created with the CRISPR/Cas system (CRISPy Critters) are being produced at an astounding pace. Animal production is no longer a significant bottleneck to new discoveries. CRISPy animal studies are just beginning to appear in the alcohol literature, but their use is expected to explode in the near future. CRISPy mice, rats, and other model organisms are sure to facilitate advances in our understanding of alcohol-use disorder.

Gene-edited CRISPy Critters for alcohol research - Homanics GE, (Alcohol, 2019)
Genetically engineered animals are powerful tools that have provided invaluable insights into mechanisms of alcohol action and alcohol-use disorder. Traditionally, production of gene-targeted animals was a tremendously expensive, time consuming, and technically demanding undertaking. However, the recent advent of facile methods for editing the genome at very high efficiency is revolutionizing how these animals are made. While pioneering approaches to create gene-edited animals first used zinc finger nucleases and subsequently used transcription activator-like effector nucleases, these approaches have been largely supplanted in an extremely short period of time with the recent discovery and precocious maturation of the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) system. CRISPR uses a short RNA sequence to guide a non-specific CRISPR-associated nuclease (Cas) to a precise, single location in the genome. Because the CRISPR/Cas system can be cheaply, rapidly, and easily reprogrammed to target nearly any genomic locus of interest simply by recoding the sequence of the guide RNA, this gene-editing system has been rapidly adopted by numerous labs around the world. With CRISPR/Cas, it is now possible to perform gene editing directly in early embryos from every species of animals that is of interest to the alcohol field. Techniques have been developed that enable the rapid production of animals in which a gene has been inactivated (knockout) or modified to harbor specific nucleotide changes (knockins). This system has also been used to insert specific DNA sequences such as reporter or recombinase genes into specific loci of interest. Genetically engineered animals created with the CRISPR/Cas system (CRISPy Critters) are being produced at an astounding pace. Animal production is no longer a significant bottleneck to new discoveries. CRISPy animal studies are just beginning to appear in the alcohol literature, but their use is expected to explode in the near future. CRISPy mice, rats, and other model organisms are sure to facilitate advances in our understanding of alcohol-use disorder.

Glial gene networks associated with alcohol dependence. - Erickson, EK; Blednov, YA; Harris, R A; Mayfield, R D (Scientific Reports, 2019)
Chronic alcohol abuse alters the molecular structure and function of brain cells. Recent work suggests adaptations made by glial cells, such as astrocytes and microglia, regulate physiological and behavioral changes associated with addiction. Defining how alcohol dependence alters the transcriptome of different cell types is critical for developing the mechanistic hypotheses necessary for a nuanced understanding of cellular signaling in the alcohol-dependent brain. We performed RNA-sequencing on total homogenate and glial cell populations isolated from mouse prefrontal cortex (PFC) following chronic intermittent ethanol vapor exposure (CIE). Compared with total homogenate, we observed unique and robust gene expression changes in astrocytes and microglia in response to CIE. Gene co-expression network analysis revealed biological pathways and hub genes associated with CIE in astrocytes and microglia that may regulate alcohol-dependent phenotypes. Astrocyte identity and synaptic calcium signaling genes were enriched in alcohol-associated astrocyte networks, while TGF-β signaling and inflammatory response genes were disrupted by CIE treatment in microglia gene networks. Genes related to innate immune signaling, specifically interferon pathways, were consistently up-regulated across CIE-exposed astrocytes, microglia, and total homogenate PFC tissue. This study illuminates the cell-specific effects of chronic alcohol exposure and provides novel molecular targets for studying alcohol dependence.

Glial gene networks associated with alcohol dependence - Erickson EK,; Blednov YA,; Harris RA; Mayfield RD (Scientific Reports, 2019)
Chronic alcohol abuse alters the molecular structure and function of brain cells. Recent work suggests adaptations made by glial cells, such as astrocytes and microglia, regulate physiological and behavioral changes associated with addiction. Defining how alcohol dependence alters the transcriptome of different cell types is critical for developing the mechanistic hypotheses necessary for a nuanced understanding of cellular signaling in the alcohol-dependent brain. We performed RNA-sequencing on total homogenate and glial cell populations isolated from mouse prefrontal cortex (PFC) following chronic intermittent ethanol vapor exposure (CIE). Compared with total homogenate, we observed unique and robust gene expression changes in astrocytes and microglia in response to CIE. Gene co-expression network analysis revealed biological pathways and hub genes associated with CIE in astrocytes and microglia that may regulate alcohol-dependent phenotypes. Astrocyte identity and synaptic calcium signaling genes were enriched in alcohol-associated astrocyte networks, while TGF-β signaling and inflammatory response genes were disrupted by CIE treatment in microglia gene networks. Genes related to innate immune signaling, specifically interferon pathways, were consistently up-regulated across CIE-exposed astrocytes, microglia, and total homogenate PFC tissue. This study illuminates the cell-specific effects of chronic alcohol exposure and provides novel molecular targets for studying alcohol dependence.

GPR88 in D1R- and D2R-Type Medium Spiny Neurons Differentially Regulates Affective and Motor Behaviors - Meirsman AC,; Ben Hamida S,; Clarke E,; de Kerchove d'Exaerde A,; Darcq E,; Kieffer BL, (eNeuro, 2019)
The orphan receptor GPR88 is highly expressed in D1R- and D2R-medium spiny neurons (MSNs) and has been associated to striatum-dependent functions in rodents. The total deletion of Gpr88 in mice was shown to decrease anxiety-like behaviors, increase stereotypies and locomotion, and impair motor coordination and motor learning. Knowing the opposing role of D1R- and D2R-MSNs, we here investigated the respective roles of GPR88 in the two MSN subtypes for these behaviors. To do so, we compared effects of a conditional Gpr88 gene knockout (KO) in D1R-MSNs (D1R-Gpr88 mice) or D2R-MSNs (A2AR-Gpr88 mice) with effects of the total Gpr88 KO (CMV-Gpr88 mice). Overall, most phenotypes of CMV-Gpr88 mice were recapitulated in A2AR-Gpr88 mice, including reduced marble burying, increased social interactions, increased locomotor activity and stereotypies in the open field, and reduced motor coordination in the rotarod. Exceptions were the reduced habituation to the open field and reduced motor skill learning, which were observed in CMV-Gpr88 and D1R-Gpr88 mice, but not in A2AR-Gpr88 mice. D1R-Gpr88 mice otherwise showed no other phenotype in this study. Our data together show that GPR88 modulates the function of both D1R- and D2R-MSNs, and that GPR88 activity in these two neuron populations has very different and dissociable impacts on behavior. We suggest that GPR88 in D2R-MSNs shapes defensive and social behavior and contributes in maintaining the inhibition of basal ganglia outputs to control locomotion, stereotypies and motor coordination, while GPR88 in D1R-MSNs promotes novelty habituation and motor learning. Significance Statement GPR88, an orphan G-protein-coupled receptor, has been implicated in the regulation of striatum-dependent behaviors. In the striatum, GPR88 is most abundant in both medium spiny neurons expressing dopamine D1 and D2 receptors. We compared effects of a conditional Gpr88 gene knockout in D1R-MSNs or D2R-MSNs with effects of the total Gpr88 deletion. Our data suggest that GPR88 in D2R-MSNs shapes defensive and social behavior and contributes in maintaining the inhibition of basal ganglia outputs to control locomotion, stereotypies and motor coordination, while GPR88 in D1R-MSNs promotes novelty habituation and motor learning. Gpr88 therefore plays very distinct roles in modulating D1R- and D2R-type neurons function and the related behaviors.

GPR88 in D1R-type and D2R-type medium spiny neurons differentially regulates affective and motor behavior. - Meirsman, AC; Ben Hamida, S; Clarke, E; de Kerchove d'Exaerde, A; Darcq, E; Kieffer, BL (eNeuro, 2019)
The orphan receptor GPR88 is highly expressed in D1 receptor (D1R)- and D2R-medium spiny neurons (MSNs) and has been associated to striatum-dependent functions in rodents. The total deletion of Gpr88 in mice was shown to decrease anxiety-like behaviors, increase stereotypies and locomotion, and impair motor coordination and motor learning. Knowing the opposing role of D1R- and D2R-MSNs, we here investigated the respective roles of GPR88 in the two MSN subtypes for these behaviors. To do so, we compared effects of a conditional Gpr88 gene knock-out (KO) in D1R-MSNs (D1R-Gpr88 mice) or D2R-MSNs (A2AR-Gpr88 mice) with effects of the total Gpr88 KO (CMV-Gpr88 mice). Overall, most phenotypes of CMV-Gpr88 mice were recapitulated in A2AR-Gpr88 mice, including reduced marble burying, increased social interactions, increased locomotor activity and stereotypies in the open field, and reduced motor coordination in the rotarod. Exceptions were the reduced habituation to the open field and reduced motor skill learning, which were observed in CMV-Gpr88 and D1R-Gpr88 mice, but not in A2AR-Gpr88 mice. D1R-Gpr88 mice otherwise showed no other phenotype in this study. Our data together show that GPR88 modulates the function of both D1R- and D2R-MSNs, and that GPR88 activity in these two neuron populations has very different and dissociable impacts on behavior. We suggest that GPR88 in D2R-MSNs shapes defensive and social behavior and contributes in maintaining the inhibition of basal ganglia outputs to control locomotion, stereotypies and motor coordination, while GPR88 in D1R-MSNs promotes novelty habituation and motor learning.

Hippocampal subfield CA2+3 exhibits accelerated aging in alcohol use disorder: a preliminary study. - Zahr, NM; Pohl, KM; Saranathan, M; Sullivan, EV; Pfefferbaum, A. (Neuroimage: Clinical, 2019)
The profile of brain structural dysmorphology of individuals with Alcohol Use Disorders (AUD) involves disruption of the limbic system. In vivo imaging studies report hippocampal volume loss in AUD relative to controls, but only recently has it been possible to articulate different regions of this complex structure. Volumetric analysis of hippocampal regions rather than total hippocampal volume may augment differentiation of disease processes. For example, damage to hippocampal subfield cornu ammonis 1 (CA1) is often reported in Alzheimer's disease (AD), whereas deficits in CA4/dentate gyrus are described in response to stress and trauma. Two previous studies explored the effects of chronic alcohol use on hippocampal subfields: one reported smaller volume of the CA2+3 in alcohol-dependent subjects relative to controls, associated with years of alcohol consumption; the other, smaller volumes of presubiculum, subiculum, and fimbria in alcohol-dependent relative to control men. The current study, conducted in 24 adults with DSM5-diagnosed AUD (7 women, 53.7 ± 8.8) and 20 controls (7 women, 54.1 ± 9.3), is the first to use FreeSurfer 6.0, which provides state-of-the art hippocampal parcellation, to explore the sensitivity of hippocampal sufields to alcoholism. T1- and T2- images were collected on a GE MR750 system with a 32-channel Nova head coil. FreeSurfer 6.0 hippocampal subfield analysis produced 12 subfields: parasubiculum; presubiculum; subiculum; CA1; CA2+3; CA4; GC-ML-DG (Granule Cell (GC) and Molecular Layer (ML) of the Dentate Gyrus (DG)); molecular layer; hippocampus-amygdala-transition-area (HATA); fimbria; hippocampal tail; hippocampal fissure; and whole volume for left and right hippocampi. A comprehensive battery of neuropsychological tests comprising attention, memory and learning, visuospatial abilities, and executive functions was administered. Multiple regression analyses of raw volumetric data for each subfields by group, age, sex, hemisphere, and supratentorial volume (svol) showed significant effects of svol (p < .04) on nearly all structures (excluding tail and fissure). Volumes corrected for svol showed effects of age (fimbria, fissure) and group (subiculum, CA1, CA4, GC-ML-DG, HATA, fimbria); CA2+3showed a diagnosis-by-age interaction indicating older AUD individuals had a smaller volume than would be expected for their age. There were no selective relations between hippocampalsubfields and performance on neuropsychological tests, likely due to lack of statistical power. The current results concur with the previous study identifying CA2+3 as sensitive to alcoholism, extend them by identifying an alcoholism-age interaction, and suggest an imaging phenotype distinguishing AUD from AD and stress/trauma.

Hippocampal subfield CA2+3 exhibits accelerated aging in Alcohol Use Disorder: A preliminary study - Zahr NM; Pohl KM; Saranathan M; Sullivan EV; Pfefferbaum A, (Neuroimage: Clinical, 2019)
The profile of brain structural dysmorphology of individuals with Alcohol Use Disorders (AUD) involves disruption of the limbic system. In vivo imaging studies report hippocampal volume loss in AUD relative to controls, but only recently has it been possible to articulate different regions of this complex structure. Volumetric analysis of hippocampal regions rather than total hippocampal volume may augment differentiation of disease processes. For example, damage to hippocampal subfield cornu ammonis 1 (CA1) is often reported in Alzheimer's disease (AD), whereas deficits in CA4/dentate gyrus are described in response to stress and trauma. Two previous studies explored the effects of chronic alcohol use on hippocampal subfields: one reported smaller volume of the CA2+3 in alcohol-dependent subjects relative to controls, associated with years of alcohol consumption; the other, smaller volumes of presubiculum, subiculum, and fimbria in alcohol-dependent relative to control men. The current study, conducted in 24 adults with DSM5-diagnosed AUD (7 women, 53.7 ± 8.8) and 20 controls (7 women, 54.1 ± 9.3), is the first to use FreeSurfer 6.0, which provides state-of-the art hippocampal parcellation, to explore the sensitivity of hippocampal sufields to alcoholism. T1- and T2- images were collected on a GE MR750 system with a 32-channel Nova head coil. FreeSurfer 6.0 hippocampal subfield analysis produced 12 subfields: parasubiculum; presubiculum; subiculum; CA1; CA2+3; CA4; GC-ML-DG (Granule Cell (GC) and Molecular Layer (ML) of the Dentate Gyrus (DG)); molecular layer; hippocampus-amygdala-transition-area (HATA); fimbria; hippocampal tail; hippocampal fissure; and whole volume for left and right hippocampi. A comprehensive battery of neuropsychological tests comprising attention, memory and learning, visuospatial abilities, and executive functions was administered. Multiple regression analyses of raw volumetric data for each subfields by group, age, sex, hemisphere, and supratentorial volume (svol) showed significant effects of svol (p < .04) on nearly all structures (excluding tail and fissure). Volumes corrected for svol showed effects of age (fimbria, fissure) and group (subiculum, CA1, CA4, GC-ML-DG, HATA, fimbria); CA2+3 showed a diagnosis-by-age interaction indicating older AUD individuals had a smaller volume than would be expected for their age. There were no selective relations between hippocampal subfields and performance on neuropsychological tests, likely due to lack of statistical power. The current results concur with the previous study identifying CA2+3 as sensitive to alcoholism, extend them by identifying an alcoholism-age interaction, and suggest an imaging phenotype distinguishing AUD from AD and stress/trauma.

The histone deacetylase inhibitor suberoylanilide hydroxamic acid (SAHA) alleviates depression-like behavior and normalizes epigenetic changes in the hippocampus during ethanol withdrawal - Chen WY; Zhang H; Gatta E; Glover EJ; Pandey SC,; Lasek AW, (Alcohol, 2019)
Withdrawal from chronic alcohol drinking can cause depression, leading to an inability to function in daily life and an increased risk for relapse to harmful drinking. Understanding the causes of alcohol withdrawal-related depression may lead to new therapeutic targets for treatment. Epigenetic factors have recently emerged as important contributors to both depression and alcohol use disorder (AUD). Specifically, acetylation of the N-terminal tails of histone proteins that package DNA into nucleosomes is altered in stress-induced models of depression and during alcohol withdrawal. The goal of this study was to examine depression-like behavior during alcohol withdrawal and associated changes in histone acetylation and expression of histone deacetylase 2 (HDAC2) in the hippocampus, a brain region critical for mood regulation and depression. Male Sprague–Dawley rats were treated with the Lieber-DeCarli ethanol liquid diet for 15 days and then underwent withdrawal. Rats were treated with the HDAC inhibitor, suberoylanilide hydroxamic acid (SAHA), during withdrawal and were tested for depression-like behavior. In a separate group of rats, the hippocampus was analyzed for mRNA and protein expression of HDAC2 and levels of histone H3 lysine 9 acetylation (H3K9ac) during chronic ethanol exposure and withdrawal. Rats undergoing ethanol withdrawal exhibited depression-like behavior and had increased HDAC2 and decreased H3K9ac levels in specific structures of the hippocampus. Treatment with SAHA during withdrawal ameliorated depression-like behavior and normalized changes in hippocampal HDAC2 and H3K9ac levels. These results demonstrate that ethanol withdrawal causes an altered epigenetic state in the hippocampus. Treatment with an HDAC inhibitor can correct this state and alleviate depression-like symptoms developed during withdrawal. Targeting histone acetylation may be a novel strategy to reduce ethanol withdrawal-induced depression.

The histone deacetylase inhibitorsuberoylanilide hydroxamic acid (SAHA) alleviates depression-like behavior and normalizes epigeneticchanges in the hippocampus during ethanol withdrawal. - Chen, WY; Zhang, H; Gatta, E; Glover, EJ; Pandey, SC; Lasek, AW (Alcohol, 2019)
Withdrawal from chronic alcohol drinking can cause depression, leading to an inability to function in daily life and an increased risk for relapse to harmful drinking. Understanding the causes of alcohol withdrawal-related depression may lead to new therapeutic targets for treatment. Epigenetic factors have recently emerged as important contributors to both depression and alcohol use disorder (AUD). Specifically, acetylation of the N-terminal tails of histone proteins that package DNA into nucleosomes is altered in stress-induced models of depression and during alcohol withdrawal. The goal of this study was to examine depression-like behavior during alcohol withdrawal and associated changes in histone acetylation and expression of histone deacetylase 2 (HDAC2) in the hippocampus, a brain region critical for mood regulation and depression. Male Sprague-Dawley rats were treated with the Lieber-DeCarli ethanol liquid diet for 15 days and then underwent withdrawal. Rats were treated with the HDAC inhibitor, suberoylanilide hydroxamic acid (SAHA), during withdrawal and were tested for depression-like behavior. In a separate group of rats, the hippocampus was analyzed for mRNA and protein expression of HDAC2 and levels of histone H3 lysine 9 acetylation (H3K9ac) during chronic ethanol exposure and withdrawal. Rats undergoing ethanol withdrawal exhibited depression-like behavior and had increased HDAC2 and decreased H3K9ac levels in specific structures of the hippocampus. Treatment with SAHA during withdrawal ameliorated depression-like behavior and normalized changes in hippocampal HDAC2 and H3K9ac levels. These results demonstrate that ethanol withdrawal causes an altered epigenetic state in the hippocampus. Treatment with an HDAC inhibitor can correct this state and alleviate depression-like symptoms developed during withdrawal. Targeting histone acetylation may be a novel strategy to reduce ethanol withdrawal-induced depression.

Identification of a functional non-coding variant in the GABA (A) receptor α2 subunit of the C57BL/6J mouse reference genome: major implications for neuroscience research - Mulligan MK,; Abreo T,; Neuner SM,; Parks C,; Watkins CE,; Houseal MT,; Shapaker TM,; Hook M,; Tan H,; Wang X,; Ingels J,; Peng J,; et al. (Frontiers in Genetics, 2019)
GABA type-A (GABA-A) receptors containing the α2 subunit (GABRA2) are expressed in most brain regions and are critical in modulating inhibitory synaptic function. Genetic variation at the GABRA2 locus has been implicated in epilepsy, affective and psychiatric disorders, alcoholism and drug abuse. Gabra2 expression varies as a function of genotype and is modulated by sequence variants in several brain structures and populations, including F2 crosses originating from C57BL/6J (B6J) and the BXD recombinant inbred family derived from B6J and DBA/2J. Here we demonstrate a global reduction of GABRA2 brain protein and mRNA in the B6J strain relative to other inbred strains, and identify and validate the causal mutation in B6J. The mutation is a single base pair deletion located in an intron adjacent to a splice acceptor site that only occurs in the B6J reference genome. The deletion became fixed in B6J between 1976 and 1991 and is now pervasive in many engineered lines, BXD strains generated after 1991, the Collaborative Cross, and the majority of consomic lines. Repair of the deletion using CRISPR-Cas9-mediated gene editing on a B6J genetic background completely restored brain levels of GABRA2 protein and mRNA. Comparison of transcript expression in hippocampus, cortex, and striatum between B6J and repaired genotypes revealed alterations in GABA-A receptor subunit expression, especially in striatum. These results suggest that naturally occurring variation in GABRA2 levels between B6J and other substrains or inbred strains may also explain strain differences in anxiety-like or alcohol and drug response traits related to striatal function. Characterization of the B6J private mutation in the Gabra2 gene is of critical importance to molecular genetic studies in neurobiological research because this strain is widely used to generate genetically engineered mice and murine genetic populations, and is the most widely utilized strain for evaluation of anxiety-like, depression-like, pain, epilepsy, and drug response traits that may be partly modulated by GABRA2 function.

Identification of a functional non-coding variant in the GABA (A) receptor α2 subunit of the C57BL/6J mouse reference genome: major implications for neuroscience research. - Mulligan MK,; Abreo T,; Neuner SM,; Parks C,; Watkins CE,; Houseal MT,; Shapaker TM,; Hook, M; Tan, H; Wang X,; Ingels J,; Peng J,; et al. (Frontiers in Genetics, 2019)
GABA type-A (GABA-A) receptors containing the α2 subunit (GABRA2) are expressed in most brain regions and are critical in modulating inhibitory synaptic function. Genetic variation at the GABRA2 locus has been implicated in epilepsy, affective and psychiatric disorders, alcoholism and drug abuse. Gabra2 expression varies as a function of genotype and is modulated by sequence variants in several brain structures and populations, including F2 crosses originating from C57BL/6J (B6J) and the BXD recombinant inbred family derived from B6J and DBA/2J. Here we demonstrate a global reduction of GABRA2 brain protein and mRNA in the B6J strain relative to other inbred strains, and identify and validate the causal mutation in B6J. The mutation is a single base pair deletion located in an intron adjacent to a splice acceptor site that only occurs in the B6J reference genome. The deletion became fixed in B6J between 1976 and 1991 and is now pervasive in many engineered lines, BXD strains generated after 1991, the Collaborative Cross, and the majority of consomic lines. Repair of the deletion using CRISPR-Cas9-mediated gene editing on a B6J genetic background completely restored brain levels of GABRA2 protein and mRNA. Comparison of transcript expression in hippocampus, cortex, and striatum between B6J and repaired genotypes revealed alterations in GABA-A receptor subunit expression, especially in striatum. These results suggest that naturally occurring variation in GABRA2 levels between B6J and other substrains or inbred strains may also explain strain differences in anxiety-like or alcohol and drug response traits related to striatal function. Characterization of the B6J private mutation in the Gabra2 gene is of critical importance to molecular genetic studies in neurobiological research because this strain is widely used to generate genetically engineered mice and murine genetic populations, and is the most widely utilized strain for evaluation of anxiety-like, depression-like, pain, epilepsy, and drug response traits that may be partly modulated by GABRA2 function.

Identification of HIVEP2 as a dopaminergic transcription factor related to substance use disorders in rats and humans - Zhao J; Chen C,; Bell RL,; Qing H; Lin Z (Translational Psychiatry, 2019)
Playing an important role in the etiology of substance use disorder (SUD), dopamine (DA) neurons are subject to various regulations but transcriptional regulations are largely understudied. For the first time, we report here that the Human Immunodeficiency Virus Type I Enhancer Binding Protein 2 (HIVEP2) is a dopaminergic transcriptional regulator. HIVEP2 is expressed in both the cytoplasm and nuclei of DA neurons. Therein, HIVEP2 can target the intronic sequence GTGGCTTTCT of SLC6A3 and thereby activate the gene. In naive rats from the bi-directional selectively bred substance-preferring P vs -nonpreferring NP rat model of substance abuse vulnerability, increased gene activity in males was associated with the vulnerability, whereas decreased gene activity in the females was associated with the same vulnerability. In clinical subjects, extensive and significant HIVEP2-SLC6A3 interactions were observed for SUD. Collectively, HIVEP2-mediated transcriptional mechanisms are implicated in dopaminergic pathophysiology of SUD.

Identification of HIVEP2 as a dopaminergic transcription factor related to substance use disorders in rats and humans. - Zhao, J; Chen, C.; Bell, RL; Qing, H; Lin, Z (Translational Psychiatry, 2019)
Playing an important role in the etiology of substance use disorder (SUD), dopamine (DA) neurons are subject to various regulations but transcriptional regulations are largely understudied. For the first time, we report here that the Human Immunodeficiency Virus Type I Enhancer Binding Protein 2 (HIVEP2) is a dopaminergic transcriptional regulator. HIVEP2 is expressed in both the cytoplasm and nuclei of DA neurons. Therein, HIVEP2 can target the intronic sequence GTGGCTTTCT of SLC6A3 and thereby activate the gene. In naive rats from the bi-directional selectively bred substance-preferring P vs -nonpreferring NP rat model of substance abuse vulnerability, increased gene activity in males was associated with the vulnerability, whereas decreased gene activity in the females was associated with the same vulnerability. In clinical subjects, extensive and significant HIVEP2-SLC6A3 interactions were observed for SUD. Collectively, HIVEP2-mediated transcriptional mechanisms are implicated in dopaminergic pathophysiology of SUD.

IL-1β expression is increased and regulates GABA transmission following chronic ethanol in mouse central amygdala - Patel RR,; Khom S,; Steinman MQ,; Varodayan FP; Kiosses WB,; Hedges DM,; Vlkolinsky R,; Nadav T,; Polis I,; Bajo M,; Roberts AJ,; Roberto M (Brain, Behavior and Immunity, 2019)
The interleukin-1 system (IL-1) is a prominent pro-inflammatory pathway responsible for the initiation and regulation of immune responses. Human genetic and preclinical studies suggest a critical role for IL-1β signaling in ethanol drinking and dependence, but little is known about the effects of chronic ethanol on the IL-1 system in addiction-related brain regions such as the central amygdala (CeA). In this study, we generated naïve, non-dependent (Non-Dep) and dependent (Dep) male mice using a paradigm of chronic-intermittent ethanol vapor exposure interspersed with two-bottle choice to examine 1) the expression of IL-1β, 2) the role of the IL-1 system on GABAergic transmission, and 3) the potential interaction with the acute effects of ethanol in the CeA. Immunohistochemistry with confocal microscopy was used to assess expression of IL-1β in microglia and neurons in the CeA, and whole-cell patch clamp recordings were obtained from CeA neurons to measure the effects of IL-1β (50 ng/ml) or the endogenous IL-1 receptor antagonist (IL-1ra; 100 ng/ml) on action potential-dependent spontaneous inhibitory postsynaptic currents (sIPSCs). Overall, we found that IL-1β expression is significantly increased in microglia and neurons of Dep compared to Non-Dep and naïve mice, IL-1β and IL-1ra bi-directionally modulate GABA transmission through both pre- and postsynaptic mechanisms in all three groups, and IL-1β and IL-1ra do not alter the facilitation of GABA release induced by acute ethanol. These data suggest that while ethanol dependence induces a neuroimmune response in the CeA, as indicated by increased IL-1β expression, this does not significantly alter the neuromodulatory role of IL-1β on synaptic transmission.

IL-1β expression is increased and regulates GABA transmission following chronic ethanol in mouse central amygdala. - Patel RR,; Khom S,; Steinman MQ,; Varodayan FP; Kiosses WB,; Hedges DM,; Vlkolinsky R,; Nadav T,; Polis I,; Bajo M,; Roberts AJ,; Roberto M (Brain, Behavior and Immunity, 2019)
The interleukin-1 system (IL-1) is a prominent pro-inflammatory pathway responsible for the initiation and regulation of immune responses. Human genetic and preclinical studies suggest a critical role for IL-1β signaling in ethanol drinking and dependence, but little is known about the effects of chronic ethanol on the IL-1 system in addiction-related brain regions such as the central amygdala (CeA). In this study, we generated naïve, non-dependent (Non-Dep) and dependent (Dep) male mice using a paradigm of chronic-intermittent ethanol vapor exposure interspersed with two-bottle choice to examine 1) the expression of IL-1β, 2) the role of the IL-1 system on GABAergic transmission, and 3) the potential interaction with the acute effects of ethanol in the CeA. Immunohistochemistry with confocal microscopy was used to assess expression of IL-1β in microglia and neurons in the CeA, and whole-cell patch clamp recordings were obtained from CeA neurons to measure the effects of IL-1β (50 ng/ml) or the endogenous IL-1 receptor antagonist (IL-1ra; 100 ng/ml) on action potential-dependent spontaneous inhibitory postsynaptic currents (sIPSCs). Overall, we found that IL-1β expression is significantly increased in microglia and neurons of Dep compared to Non-Dep and naïve mice, IL-1β and IL-1ra bi-directionally modulate GABA transmission through both pre- and postsynaptic mechanisms in all three groups, and IL-1β and IL-1ra do not alter the facilitation of GABA release induced by acute ethanol. These data suggest that while ethanol dependence induces a neuroimmune response in the CeA, as indicated by increased IL-1β expression, this does not significantly alter the neuromodulatory role of IL-1β on synaptic transmission.

Inactivation of a CRF-dependent amygdalofugal pathway reverses addiction-like behaviors in alcohol-dependent rats. - de Guglielmo, G; Kallupi, M; Pomrenze, MB; Crawford, E; Simpson, S; Schweitzer, P; Koob, GF; Messing, RO; George, O. (Nature Communications, 2019)
The activation of a neuronal ensemble in the central nucleus of the amygdala (CeA) during alcohol withdrawal has been hypothesized to induce high levels of alcohol drinking in dependent rats. In the present study we describe that the CeA neuronal ensemble that is activated by withdrawal from chronic alcohol exposure contains ~80% corticotropin-releasing factor (CRF) neurons and that the optogenetic inactivation of these CeA CRF+ neurons prevents recruitment of the neuronal ensemble, decreases the escalation of alcohol drinking, and decreases the intensity of somatic signs of withdrawal. Optogenetic dissection of the downstream neuronal pathways demonstrates that the reversal of addiction-likebehaviors is observed after the inhibition of CeA CRF projections to the bed nucleus of the stria terminalis (BNST) and that inhibition of the CRFCeA-BNST pathway is mediated by inhibition of the CRF-CRF1 system and inhibition of BNST cell firing. These results suggest that the CRFCeA-BNST pathway could be targeted for the treatment of excessive drinking in alcohol use disorder.

Inactivation of a CRF-dependent amygdalofugal pathway reverses addiction-like behaviors in alcohol-dependent rats - de Guglielmo G,; Kallupi M,; Pomrenze MB,; Crawford E,; Simpson S,; Schweitzer P,; Koob GF,; Messing RO,; George O (Nature Communications, 2019)
The activation of a neuronal ensemble in the central nucleus of the amygdala (CeA) during alcohol withdrawal has been hypothesized to induce high levels of alcohol drinking in dependent rats. In the present study we describe that the CeA neuronal ensemble that is activated by withdrawal from chronic alcohol exposure contains ~80% corticotropin-releasing factor (CRF) neurons and that the optogenetic inactivation of these CeA CRF+ neurons prevents recruitment of the neuronal ensemble, decreases the escalation of alcohol drinking, and decreases the intensity of somatic signs of withdrawal. Optogenetic dissection of the downstream neuronal pathways demonstrates that the reversal of addiction-like behaviors is observed after the inhibition of CeA CRF projections to the bed nucleus of the stria terminalis (BNST) and that inhibition of the CRFCeA-BNST pathway is mediated by inhibition of the CRF-CRF1 system and inhibition of BNST cell firing. These results suggest that the CRFCeA-BNST pathway could be targeted for the treatment of excessive drinking in alcohol use disorder.

Increased IL-6 expression in astrocytes is associated with emotionality, alterations in central amygdala GABAergic transmission, and excitability during alcohol withdrawal. - Roberts, AJ; Khom, S; Bajo, M; Vlkolinsky, R; Polis, I; Cates-Gatto, C; Roberto, M; Gruol, DL (Brain Behavior and Immunity, 2019)
Accumulating evidence from preclinical and clinical studies has implicated a role for the cytokine IL-6 in a variety of CNS diseases including anxiety-like and depressive-like behaviors, as well as alcohol use disorder. Here we use homozygous and heterozygous transgenic mice expressing elevated levels of IL-6 in the CNS due to increased astrocyte expression and non-transgenic littermates to examine a role for astrocyte-produced IL-6 in emotionality (response to novelty, anxiety-like, and depressive-like behaviors). Our results from homozygous IL-6 mice in a variety of behavioral tests (light/dark transfer, open field, digging, tail suspension, and forced swim tests) support a role for IL-6 in stress-coping behaviors. Ex vivo electrophysiological studies of neuronal excitability and inhibitory GABAergic synaptic transmission in the central nucleus of the amygdala (CeA) of the homozygous transgenic mice revealed increased inhibitory GABAergic signaling and increased excitability of CeA neurons, suggesting a role for astrocyte produced IL-6 in the amygdala in exploratory drive and depressive-like behavior. Furthermore, studies in the hippocampus of activation/expression of proteins associated with IL-6 signal transduction and inhibitory GABAergic mechanisms support a role for astrocyte produced IL-6 in depressive-like behaviors. Our studies indicate a complex and dose-dependent relationship between IL-6 and behavior and implicate IL-6 induced neuroadaptive changes in neuronal excitability and the inhibitory GABAergic system as important contributors to altered behavior associated with IL-6 expression in the CNS.

Increased IL-6 expression in astrocytes is associated with emotionality, alterations in central amygdala GABAergic transmission, and excitability during alcohol withdrawalv - Roberts AJ,; Khom S,; Bajo M,; Vlkolinsky R,; Polis I,; Cates-Gatto C,; Roberto M; Gruol DL (Brain Behavior and Immunity, 2019)
Accumulating evidence from preclinical and clinical studies has implicated a role for the cytokine IL-6 in a variety of CNS diseases including anxiety-like and depressive-like behaviors, as well as alcohol use disorder. Here we use homozygous and heterozygous transgenic mice expressing elevated levels of IL-6 in the CNS due to increased astrocyte expression and non-transgenic littermates to examine a role for astrocyte-produced IL-6 in emotionality (response to novelty, anxiety-like, and depressive-like behaviors). Our results from homozygous IL-6 mice in a variety of behavioral tests (light/dark transfer, open field, digging, tail suspension, and forced swim tests) support a role for IL-6 in stress-coping behaviors. Ex vivo electrophysiological studies of neuronal excitability and inhibitory GABAergic synaptic transmission in the central nucleus of the amygdala (CeA) of the homozygous transgenic mice revealed increased inhibitory GABAergic signaling and increased excitability of CeA neurons, suggesting a role for astrocyte produced IL-6 in the amygdala in exploratory drive and depressive-like behavior. Furthermore, studies in the hippocampus of activation/expression of proteins associated with IL-6 signal transduction and inhibitory GABAergic mechanisms support a role for astrocyte produced IL-6 in depressive-like behaviors. Our studies indicate a complex and dose-dependent relationship between IL-6 and behavior and implicate IL-6 induced neuroadaptive changes in neuronal excitability and the inhibitory GABAergic system as important contributors to altered behavior associated with IL-6 expression in the CNS.

Intergenerational Effects of Alcohol: A Review of Paternal Preconception Ethanol Exposure Studies and Epigenetic Mechanisms in the Male Germline - Rompala GR; Homanics GE, (Alcoholism: Clinical and Experimental Research, 2019)
While alcohol use disorder (AUD) is a highly heritable psychiatric disease, efforts to elucidate that heritability by examining genetic variation (e.g., single nucleotide polymorphisms) have been insufficient to fully account for familial AUD risk. Perhaps not coincidently, there has been a burgeoning interest in novel nongenomic mechanisms of inheritance (i.e., epigenetics) that are shaped in the male or female germ cells by significant lifetime experiences such as exposure to chronic stress, malnutrition, or drugs of abuse. While many epidemiological and preclinical studies have long pointed to a role for the parental preconception environment in offspring behavior, over the last decade many studies have implicated a causal relationship between the environmentally sensitive sperm epigenome and intergenerational phenotypes. This critical review will detail the heritable effects of alcohol and the potential role for epigenetics.

Intergenerational effects of alcohol: a review of paternal preconception ethanol exposure studies and epigenetic mechanisms in the male germline. - Rompala, GR; Homanics, GE (Alcoholism: Clinical and Experimental Research, 2019)
While alcohol use disorder (AUD) is a highly heritable psychiatric disease, efforts to elucidate that heritability by examining genetic variation (e.g., single nucleotide polymorphisms) have been insufficient to fully account for familial AUD risk. Perhaps not coincidently, there has been a burgeoning interest in novel nongenomic mechanisms of inheritance (i.e., epigenetics) that are shaped in the male or female germ cells by significant lifetime experiences such as exposure to chronic stress, malnutrition, or drugs of abuse. While many epidemiological and preclinical studies have long pointed to a role for the parental preconception environment in offspring behavior, over the last decade many studies have implicated a causal relationship between the environmentally sensitive sperm epigenome and intergenerational phenotypes. This critical review will detail the heritable effects of alcohol and the potential role for epigenetics.

Molecular, Morphological, and Functional Characterization of Corticotropin-Releasing Factor Receptor 1-Expressing Neurons in the Central Nucleus of the Amygdala - Wolfe SA,; Sidhu H; Patel RR,; Kreifeldt M; D'Ambrosio SR,; Contet C; Roberto M (eNeuro, 2019)
The central nucleus of the amygdala (CeA) is a brain region implicated in anxiety, stress-related disorders and the reinforcing effects of drugs of abuse. Corticotropin-releasing factor (CRF, Crh) acting at cognate type 1 receptors (CRF1, Crhr1) modulates inhibitory and excitatory synaptic transmission in the CeA. Here, we used CRF1:GFP reporter mice to characterize the morphological, neurochemical and electrophysiological properties of CRF1-expressing (CRF1+) and CRF1-non-expressing (CRF1–) neurons in the CeA. We assessed these two neuronal populations for distinctions in the expression of GABAergic subpopulation markers and neuropeptides, dendritic spine density and morphology, and excitatory transmission. We observed that CeA CRF1+ neurons are GABAergic but do not segregate with calbindin (CB), calretinin (CR), parvalbumin (PV), or protein kinase C-δ (PKCδ). Among the neuropeptides analyzed, Penk and Sst had the highest percentage of co-expression with Crhr1 in both the medial and lateral CeA subdivisions. Additionally, CeA CRF1+ neurons had a lower density of dendritic spines, which was offset by a higher proportion of mature spines compared to neighboring CRF1– neurons. Accordingly, there was no difference in basal spontaneous glutamatergic transmission between the two populations. Application of CRF increased overall vesicular glutamate release onto both CRF1+ and CRF1– neurons and does not affect amplitude or kinetics of EPSCs in either population. These novel data highlight important differences in the neurochemical make-up and morphology of CRF1+ compared to CRF1– neurons, which may have important implications for the transduction of CRF signaling in the CeA. Keywords: calcium binding proteins, corticotropin-releasing factor, dendritic spines, glutamatergic signaling, neuropeptides, stress and anxiety

Mu opioid receptors in GABAergic neurons of the forebrain promote alcohol reward and drinking - Ben Hamida S,; Boulos LJ,; McNicholas M,; Charbogne P,; Kieffer BL, (Addiction Biology, 2019)
Mu opioid receptors (MORs) are widely distributed throughout brain reward circuits and their role in drug and social reward is well established. Substantial evidence has implicated MOR and the endogenous opioid system in alcohol reward, but circuit mechanisms of MOR‐mediated alcohol reward and intake behavior remain elusive, and have not been investigated by genetic approaches. We recently created conditional knockout (KO) mice targeting the Oprm1 gene in GABAergic forebrain neurons. These mice (Dlx‐MOR KO) show a major MOR deletion in the striatum, whereas receptors in midbrain (including the Ventral Tegmental Area or VTA) and hindbrain are intact. Here, we compared alcohol‐drinking behavior and rewarding effects in total (MOR KO) and conditional KO mice. Concordant with our previous work, MOR KO mice drank less alcohol in continuous and intermittent two‐bottle choice protocols. Remarkably, Dlx‐MOR KO mice showed reduced drinking similar to MOR KO mice, demonstrating that MOR in the forebrain is responsible for the observed phenotype. Further, alcohol‐induced conditioned place preference was detected in control but not MOR KO mice, indicating that MOR is essential for alcohol reward and again, Dlx‐MOR KO recapitulated the MOR KO phenotype. Taste preference and blood alcohol levels were otherwise unchanged in mutant lines. Together, our data demonstrate that MOR expressed in forebrain GABAergic neurons is essential for alcohol reward‐driven behaviors, including drinking and place conditioning. Challenging the prevailing VTA‐centric hypothesis, this study reveals another mechanism of MOR‐mediated alcohol reward and consumption, which does not necessarily require local VTA MORs but rather engages striatal MOR‐dependent mechanisms.

Mu opioid receptors in GABAergic neurons of the forebrain promote alcohol reward and drinking - Hamida B,; Boulos, LJ.,; McNicholas, M.,; Charbogne, P.,; Kieffer BL, (Addiction Biology, 2019)
Mu opioid receptors (MORs) are widely distributed throughout brain reward circuits and their role in drug and social reward is well established. Substantial evidence has implicated MOR and the endogenous opioid system in alcohol reward, but circuit mechanisms of MOR‐mediated alcohol reward and intake behavior remain elusive, and have not been investigated by genetic approaches. We recently created conditional knockout (KO) mice targeting the Oprm1 gene in GABAergic forebrain neurons. These mice (Dlx‐MOR KO) show a major MOR deletion in the striatum, whereas receptors in midbrain (including the Ventral Tegmental Area or VTA) and hindbrain are intact. Here, we compared alcohol‐drinking behavior and rewarding effects in total (MOR KO) and conditional KO mice. Concordant with our previous work, MOR KO mice drank less alcohol in continuous and intermittent two‐bottle choice protocols. Remarkably, Dlx‐MOR KO mice showed reduced drinking similar to MOR KO mice, demonstrating that MOR in the forebrain is responsible for the observed phenotype. Further, alcohol‐induced conditioned place preference was detected in control but not MOR KO mice, indicating that MOR is essential for alcohol reward and again, Dlx‐MOR KO recapitulated the MOR KO phenotype. Taste preference and blood alcohol levels were otherwise unchanged in mutant lines. Together, our data demonstrate that MOR expressed in forebrain GABAergic neurons is essential for alcohol reward‐driven behaviors, including drinking and place conditioning. Challenging the prevailing VTA‐centric hypothesis, this study reveals another mechanism of MOR‐mediated alcohol reward and consumption, which does not necessarily require local VTA MORs but rather engages striatal MOR‐dependent mechanisms.

Neuroimmune signaling in alcohol use disorder - Erickson EK,; Grantham EK,; Warden AS,; Harris RA (Pharmacology Biochemistry and Behavior, 2019)
Alcohol use disorder (AUD) is a widespread disease with limited treatment options. Targeting the neuroimmune system is a new avenue for developing or repurposing effective pharmacotherapies. Alcohol modulates innate immune signaling in different cell types in the brain by altering gene expression and the molecular pathways that regulate <a href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/nervous-system-inflammation" title="Learn more about Nervous System Inflammation from ScienceDirect's AI-generated Topic Pages">neuroinflammation. Chronic alcohol abuse may cause an imbalance in neuroimmune function, resulting in prolonged perturbations in brain function. Likewise, manipulating the neuroimmune system may change alcohol-related behaviors. Psychiatric disorders that are comorbid with AUD, such as <a href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/posttraumatic-stress-disorder" title="Learn more about Posttraumatic Stress Disorder from ScienceDirect's AI-generated Topic Pages">post-traumatic stress disorder, major depressive disorder, and other substance use disorders, may also have underlying neuroimmune mechanisms; current evidence suggests that convergent immune pathways may be involved in AUD and in these comorbid disorders. In this review, we provide an overview of major neuroimmune cell-types and pathways involved in mediating alcohol behaviors, discuss potential mechanisms of alcohol-induced neuroimmune activation, and present recent clinical evidence for candidate immune-related drugs to treat AUD.

Neuroimmune signaling in alcohol use disorder - Erickson EK,; Grantham EK,; Warden AS,; Harris, R A (Pharmacology Biochemistry and Behavior, 2019)
Alcohol use disorder (AUD) is a widespread disease with limited treatment options. Targeting the neuroimmune system is a new avenue for developing or repurposing effective pharmacotherapies. Alcohol modulates innate immune signaling in different cell types in the brain by altering gene expression and the molecular pathways that regulate neuroinflammation. Chronic alcohol abuse may cause an imbalance in neuroimmune function, resulting in prolonged perturbations in brain function. Likewise, manipulating the neuroimmune system may change alcohol-related behaviors. Psychiatric disorders that are comorbid with AUD, such as post-traumatic stress disorder, major depressive disorder, and other substance use disorders, may also have underlying neuroimmune mechanisms; current evidence suggests that convergent immune pathways may be involved in AUD and in these comorbid disorders. In this review, we provide an overview of major neuroimmune cell-types and pathways involved in mediating alcohol behaviors, discuss potential mechanisms of alcohol-induced neuroimmune activation, and present recent clinical evidence for candidate immune-related drugs to treat AUD.

Neurological, nutritional and alcohol consumption factors underlie cognitive and motor deficits in chronic alcoholism - Fama R,; Le Berre AP,; Hardcastle C,; Sassoon SA,; Pfefferbaum A,; Sullivan EV; Zahr NM (Addiction Biology, 2019)
Variations in pattern and extent of cognitive and motor impairment occur in alcoholism (ALC). Causes of such heterogeneity are elusive and inconsistently accounted for by demographic or alcohol consumption differences. We examined neurological and nutritional factors as possible contributors to heterogeneity in impairment. Participants with ALC (n = 96) and a normal comparison group (n = 41) were examined on six cognitive and motor domains. Signs of historically determined subclinical Wernicke's encephalopathy were detected using the Caine et al. criteria, which were based on postmortem examination and chart review of antemortem data of alcoholic cases with postmortem evidence for Wernicke's encephalopathy. Herein, four Caine criteria provided quantification of dietary deficiency, cerebellar dysfunction, low general cognitive functioning and oculomotor abnormalities in 86 of the 96 ALC participants. Subgroups based on Caine criteria yielded a graded effect, where those meeting more criteria exhibited greater impairment than those meeting no to fewer criteria. These results could not be accounted for by history of drug dependence. Multiple regression indicated that compromised performance on ataxia, indicative of cerebellar dysfunction, predicted non‐mnemonic and upper motor deficits, whereas low whole blood thiamine level, consistent with limbic circuit dysfunction, predicted mnemonic deficits. This double dissociation indicates biological markers that contribute to heterogeneity in expression of functional impairment in ALC. That non‐mnemonic and mnemonic deficits are subserved by the dissociable neural systems of frontocerebellar and limbic circuitry, both commonly disrupted in ALC, suggests neural mechanisms that can differentially affect selective functions, thereby contributing to heterogeneity in pattern and extent of dysfunction in ALC.

Neurological, nutritional and alcohol consumption factors underlie cognitive and motor deficits in chronic alcoholism - Fama R,; Le Berre AP,; Hardcastle C,; Sassoon SA,; Pfefferbaum A,; Sullivan, EV; Zahr, NM (Addiction Biology, 2019)
Variations in pattern and extent of cognitive and motor impairment occur in alcoholism (ALC). Causes of such heterogeneity are elusive and inconsistently accounted for by demographic or alcohol consumption differences. We examined neurological and nutritional factors as possible contributors to heterogeneity in impairment. Participants with ALC (n = 96) and a normal comparison group (n = 41) were examined on six cognitive and motor domains. Signs of historically determined subclinical Wernicke's encephalopathy were detected using the Caine et al. criteria, which were based on postmortem examination and chart review of antemortem data of alcoholic cases with postmortem evidence for Wernicke's encephalopathy. Herein, four Caine criteria provided quantification of dietary deficiency, cerebellar dysfunction, low general cognitive functioning and oculomotor abnormalities in 86 of the 96 ALC participants. Subgroups based on Caine criteria yielded a graded effect, where those meeting more criteria exhibited greater impairment than those meeting no to fewer criteria. These results could not be accounted for by history of drug dependence. Multiple regression indicated that compromised performance on ataxia, indicative of cerebellar dysfunction, predicted non-mnemonic and upper motor deficits, whereas low whole blood thiamine level, consistent with limbic circuit dysfunction, predicted mnemonic deficits. This double dissociation indicates biological markers that contribute to heterogeneity in expression of functional impairment in ALC. That non-mnemonic and mnemonic deficits are subserved by the dissociable neural systems of frontocerebellar and limbic circuitry, both commonly disrupted in ALC, suggests neural mechanisms that can differentially affect selective functions, thereby contributing to heterogeneity in pattern and extent of dysfunction in ALC.

A Pathway-Based Genomic Approach to Identify Medications: Application to Alcohol Use Disorder - Ferguson LB,; Patil S,; Moskowitz BA,; Ponomarev I,; Harris RA; Mayfield RD; Messing RO, (Brain Sciences, 2019)
Chronic, excessive alcohol use alters brain gene expression patterns, which could be important for initiating, maintaining, or progressing the addicted state. It has been proposed that pharmaceuticals with opposing effects on gene expression could treat alcohol use disorder (AUD). Computational strategies comparing gene expression signatures of disease to those of pharmaceuticals show promise for nominating novel treatments. We reasoned that it may be sufficient for a treatment to target the biological pathway rather than lists of individual genes perturbed by AUD. We analyzed published and unpublished transcriptomic data using gene set enrichment of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways to identify biological pathways disrupted in AUD brain and by compounds in the Library of Network-based Cellular Signatures (LINCS L1000) and Connectivity Map (CMap) databases. Several pathways were consistently disrupted in AUD brain, including an up-regulation of genes within the Complement and Coagulation Cascade, Focal Adhesion, Systemic Lupus Erythematosus, and MAPK signaling, and a down-regulation of genes within the Oxidative Phosphorylation pathway, strengthening evidence for their importance in AUD. Over 200 compounds targeted genes within those pathways in an opposing manner, more than twenty of which have already been shown to affect alcohol consumption, providing confidence in our approach. We created a user-friendly web-interface that researchers can use to identify drugs that target pathways of interest or nominate mechanism of action for drugs. This study demonstrates a unique systems pharmacology approach that can nominate pharmaceuticals that target pathways disrupted in disease states such as AUD and identify compounds that could be repurposed for AUD if sufficient evidence is attained in preclinical studies

Peri-adolescent alcohol consumption increases sensitivity and dopaminergic response to nicotine during adulthood in female alcohol-preferring (P) rats: Alterations to α7 nicotinic acetylcholine receptor expression. - Waeiss, RA; Knight, CP; Carvajal, GB; Bell, RL; Engleman, EA; McBride, WJ; Hauser, SR; Rodd, ZA (Behavioural Brain Research, 2019)
Adolescent alcohol drinking has been linked to increased risk for drug abuse during adulthood. Nicotine microinjected directly into the posterior ventral tegmental area (pVTA) stimulates dopamine (DA) release in the nucleus accumbens (NAc) shell. The α7 nicotinic acetylcholine receptor (nAChR) is a potent regulator of dopaminergic activity in the pVTA. The current experiments examined the effects of peri-adolescent ethanol (EtOH) drinking on the ability of intra-pVTA nicotine to stimulate DA release during adulthood and alterations in α7 nAChR expression within the pVTA. Alcohol-preferring (P) female rats consumed EtOH and/or water during adolescence (post-natal day [PND] 30-60) or adulthood (PND 90-120). Thirty days following removal of EtOH, subjects received microinjections of 1 μM, 10 μM, or 50 μM nicotine into the pVTA concurrently with microdialysis for extracellular DA in the NAc shell. Brains were harvested from an additional cohort after PND 90 for quantification of α7 nAChR within the pVTA. The results indicated that only adolescent EtOH consumption produced a leftward and upward shift in the dose response curve for nicotine to stimulate DA release in the NAc shell. Investigation of α7 nAChR expression within the pVTA revealed a significant increase in animals that consumed EtOH during adolescence compared to naïve animals. The data suggests that peri-adolescent EtOH consumption produced cross-sensitization to the effects of nicotine during adulthood. The interaction between adolescent EtOH consumption and inflated adult risk for drug dependency could be predicated, at least in part, upon alterations in α7 nAChR expression within the mesolimbic reward pathway.

Peri-adolescent alcohol consumption increases sensitivity and dopaminergic response to nicotine during adulthood in female alcohol-preferring (P) rats: Alterations to α7 nicotinic acetylcholine receptor expression - Waeiss RA,; Knight CP,; Carvajal GB,; Bell RL,; Engleman EA,; McBride WJ,; Hauser SR,; Rodd ZA (Behavioural Brain Research, 2019)
Adolescent alcohol drinking has been linked to increased risk for drug abuse during adulthood. Nicotine microinjected directly into the posterior ventral tegmental area (pVTA) stimulates dopamine (DA) release in the nucleus accumbens (NAc) shell. The α7 nicotinic acetylcholine receptor (nAChR) is a potent regulator of dopaminergic activity in the pVTA. The current experiments examined the effects of peri-adolescent ethanol (EtOH) drinking on the ability of intra-pVTA nicotine to stimulate DA release during adulthood and alterations in α7 nAChR expression within the pVTA. Alcohol-preferring (P) female rats consumed EtOH and/or water during adolescence (post-natal day [PND] 30–60) or adulthood (PND 90–120). Thirty days following removal of EtOH, subjects received microinjections of 1 μM, 10 μM, or 50 μM nicotine into the pVTA concurrently with microdialysis for extracellular DA in the NAc shell. Brains were harvested from an additional cohort after PND 90 for quantification of α7 nAChR within the pVTA. The results indicated that only adolescent EtOH consumption produced a leftward and upward shift in the dose response curve for nicotine to stimulate DA release in the NAc shell. Investigation of α7 nAChR expression within the pVTA revealed a significant increase in animals that consumed EtOH during adolescence compared to naïve animals. The data suggests that peri-adolescent EtOH consumption produced cross-sensitization to the effects of nicotine during adulthood. The interaction between adolescent EtOH consumption and inflated adult risk for drug dependency could be predicated, at least in part, upon alterations in α7 nAChR expression within the mesolimbic reward pathway.

Role of MyD88 in IL-1β and ethanol modulation of GABAergic transmission in the central amygdala. - Bajo M,; Patel RR,; Hedges DM,; Varodayan FP; Vlkolinsky R,; Davis TD,; Burkart MD,; Blednov YA,; Roberto M (Brain Sciences, 2019)
Myeloid differentiation primary response protein (MyD88) is a critical neuroimmune adaptor protein in TLR (Toll-like receptor) and IL-1R (Interleukin-1 receptor) signaling complexes. These two pro-inflammatory families play an important role in the neurobiology of alcohol use disorder, specifically MyD88 regulates ethanol drinking, ethanol-induced sedation, and ethanol-induced deficits in motor coordination. In this study, we examined the role of MyD88 in mediating the effects of IL-1β and ethanol on GABAergic transmission in the central amygdala (CeA) of male mice using whole-cell patch-clamp recordings in combination with pharmacological (AS-1, a mimetic that prevents MyD88 recruitment by IL-1R) and genetic (Myd88 knockout mice) approaches. We demonstrate through both approaches that IL-1β and ethanol’s modulatory effects at CeA GABA synapses are not dependent on MyD88. Myd88 knockout potentiated IL-1β’s actions in reducing postsynaptic GABAA receptor function. Pharmacological inhibition of MyD88 modulates IL-1β’s action at CeA GABA synapses similar to Myd88 knockout mice. Additionally, ethanol-induced CeA GABA release was greater in Myd88 knockout mice compared to wildtype controls. Thus, MyD88 is not essential to IL-1β or ethanol regulation of CeA GABA synapses but plays a role in modulating the magnitude of their effects, which may be a potential mechanism by which it regulates ethanol-related behaviors

Scn4b regulates the hypnotic effects of ethanol and other sedative drugs - Blednov YA,; Bajo M,; Roberts AJ,; Da Costa AJ,; Black M,; Edmunds S,; Mayfield J,; Roberto M; Homanics GE,; Lasek AW,; Hitzemann RJ,; Harris RA (Genes Brain and Behavior, 2019)
The voltage-gated sodium channel subunit β4 (SCN4B) regulates neuronal activity by modulating channel gating and has been implicated in ethanol consumption in rodent models and human alcoholics. However, the functional role for Scn4b in ethanol-mediated behaviors is unknown. We determined if genetic global knockout or targeted knockdown of Scn4b in the central nucleus of the amygdala (CeA) altered ethanol drinking or related behaviors. We used four different ethanol consumption procedures (continuous and intermittent two-bottle choice, drinking-in-the dark, and chronic intermittent ethanol vapor) and found that male and female Scn4b knockout mice did not differ from their wild-type littermates in ethanol consumption in any of the tests. Knockdown of Scn4b mRNA in the CeA also did not alter two-bottle choice ethanol drinking. However, Scn4b knockout mice demonstrated longer duration of the loss of righting reflex induced by ethanol, gaboxadol, pentobarbital, and ketamine. Knockout mice showed slower recovery to basal levels of handling-induced convulsions after ethanol injection, which is consistent with the increased sedative effects observed in these mice. However, Scn4b knockout mice did not differ in the severity of acute ethanol withdrawal. Acoustic startle responses, ethanol-induced hypothermia, and clearance of blood ethanol also did not differ between the genotypes. There were also no functional differences in the membrane properties or excitability of CeA neurons from Scn4b knockout and wild-type mice. Although we found no evidence that Scn4b regulates ethanol consumption in mice, it was involved in the acute hypnotic effects of ethanol and other sedatives.

Scn4b regulates the hypnotic effects of ethanol and other sedative drugs - Blednov YA,; Bajo M,; Roberts AJ,; Da Costa AJ,; Black M,; Edmunds S,; Mayfield J,; Roberto M; Homanics GE,; Lasek AW,; Hitzemann RJ,; Harris RA (Genes Brain and Behavior, 2019)
The voltage‐gated sodium channel subunit β4 (SCN4B) regulates neuronal activity by modulating channel gating and has been implicated in ethanol consumption in rodent models and human alcoholics. However, the functional role for Scn4b in ethanol‐mediated behaviors is unknown. We determined if genetic global knockout (KO) or targeted knockdown of Scn4b in the central nucleus of the amygdala (CeA) altered ethanol drinking or related behaviors. We used four different ethanol consumption procedures (continuous and intermittent two‐bottle choice (2BC), drinking‐in‐the dark and chronic intermittent ethanol vapor) and found that male and female Scn4b KO mice did not differ from their wild‐type (WT) littermates in ethanol consumption in any of the tests. Knockdown of Scn4b mRNA in the CeA also did not alter 2BC ethanol drinking. However, Scn4b KO mice showed longer duration of the loss of righting reflex induced by ethanol, gaboxadol, pentobarbital and ketamine. KO mice showed slower recovery to basal levels of handling‐induced convulsions after ethanol injection, which is consistent with the increased sedative effects observed in these mice. However, Scn4b KO mice did not differ in the severity of acute ethanol withdrawal. Acoustic startle responses, ethanol‐induced hypothermia and clearance of blood ethanol also did not differ between the genotypes. There were also no functional differences in the membrane properties or excitability of CeA neurons from Scn4b KO and WT mice. Although we found no evidence that Scn4b regulates ethanol consumption in mice, it was involved in the acute hypnotic effects of ethanol and other sedatives.

Sex differences in cognitive performance and alcohol consumption in High Alcohol-Drinking (HAD-1) rats - Mittal N,; Fleming SM,; Martinez A,; Thakore N,; Bell RL,; Maddox WT,; Schallert T,; Duvauchelle CL (Behavioural Brain Research, 2019)
Excessive alcohol (ethanol) consumption negatively impacts social, emotional, as well as cognitive function and well-being. Thus, identifying behavioral and/or biological predictors of excessive ethanol consumption is important for developing prevention and treatment strategies against alcohol use disorders (AUDs). Sex differences in alcohol consumption patterns are observed in humans, primates, and rodents. Selectively bred high alcohol-drinking rat lines, such as the “HAD-1” lines are recognized animal models of alcoholism. The present work examined sex differences in alcohol consumption, object recognition, and exploratory behavior in male and female HAD-1 rats. Naïve male and female HAD-1 rats were tested in an object recognition test (ORT) prior to a chronic 24 h intermittent ethanol access procedure for five weeks. Object recognition parameters measured included exploratory behavior, object investigation, and time spent near objects. During the initial training trial, rearing, active object investigation and amount of time spent in the object-containing section was significantly greater in female HAD-1 rats compared to their male counterparts. During the subsequent testing trial, time spent in the object-containing section was greater in female, compared to male, rats; but active object investigation and rearing did not statistically differ between females and males. In addition, female HAD-1 rats consumed significantly more ethanol than their male counterparts, replicating previous findings. Moreover, across all animals there was a significant positive correlation between exploratory behavior in ORT and ethanol consumption level. These results indicate there are significant sex differences in cognitive performance and alcohol consumption in HAD-1 rats, which suggests neurobiological differences as well.

Sex-specific ultrasonic vocalization patterns and alcohol consumption in high alcohol-drinking (HAD-1) rats - Mittal N,; Thakore N,; Bell RL,; Maddox WT,; Schallert T,; Duvauchelle CL (Physiology and Behavior, 2019)
Ultrasonic vocalizations (USVs) have been established as an animal model of emotional status and are often utilized in drug abuse studies as motivational and emotional indices. Further USV functionality has been demonstrated in our recent work showing accurate identification of selectively-bred high versus low alcohol-consuming male rats ascertained exclusively from 22 to 28 kHz and 50–55 kHz FM USV acoustic parameters. With the hypothesis that alcohol-sensitive sex differences could be revealed through USV acoustic parameters, the present study examined USVs and alcohol consumption in male and female selectively bred high-alcohol drinking (HAD-1) rats. For the current study, we examined USV data collected during a 12-week experiment in male and female HAD-1 rats. Experimental phases included Baseline (2 weeks), 4-h EtOH Access (4 weeks), 24-h EtOH Access (4 weeks) and Abstinence (2 weeks). Findings showed that both male and female HAD-1 rats spontaneously emitted a large number of 22–28 kHz and 50–55 kHz FM USVs and that females drank significantly more alcohol compared to males over the entire course of the experiment. Analyses of USV acoustic characteristics (i.e. mean frequency, duration, bandwidth and power) revealed distinct sex-specific phenotypes in both 50–55 kHz FM and 22–28 kHz USV transmission that were modulated by ethanol exposure. Moreover, by using a linear combination of these acoustic characteristics, we were able to develop binomial logistic regression models able to discriminate between male and female HAD-1 rats with high accuracy. Together these results highlight unique emotional phenotypes in male and female HAD-1 rats that are differentially modulated by alcohol experience.

Sex-specific ultrasonic vocalization patterns and alcohol consumption in high alcohol-drinking (HAD-1) rats. - Mittal N,; Thakore N,; Bell RL,; Maddox WT,; Schallert T,; Duvauchelle, CL (Physiology and Behavior, 2019)
Ultrasonic vocalizations (USVs) have been established as an animal model of emotional status and are often utilized in drug abuse studies as motivational and emotional indices. Further USV functionality has been demonstrated in our recent work showing accurate identification of selectively-bred high versus low alcohol-consuming male rats ascertained exclusively from 22 to 28kHz and 50-55kHz FM USV acoustic parameters. With the hypothesis that alcohol-sensitive sex differences could be revealed through USV acoustic parameters, the present study examined USVs and alcohol consumption in male and female selectively bred high-alcohol drinking (HAD-1) rats. For the current study, we examined USV data collected during a 12-week experiment in male and female HAD-1 rats. Experimental phases included Baseline (2weeks), 4-h EtOH Access (4weeks), 24-h EtOH Access (4weeks) and Abstinence (2weeks). Findings showed that both male and female HAD-1 rats spontaneously emitted a large number of 22-28kHz and 50-55kHz FM USVs and that females drank significantly more alcohol compared to males over the entire course of the experiment. Analyses of USV acoustic characteristics (i.e. mean frequency, duration, bandwidth and power) revealed distinct sex-specific phenotypes in both 50-55kHz FM and 22-28kHz USV transmission that were modulated by ethanol exposure. Moreover, by using a linear combination of these acoustic characteristics, we were able to develop binomial logistic regression models able to discriminate between male and female HAD-1 rats with high accuracy. Together these results highlight unique emotional phenotypes in male and female HAD-1 rats that are differentially modulated by alcohol experience.

Silencing synaptic MicroRNA-411 reduces voluntary alcohol consumption in mice. - Most, D; Salem, NA; Tiwari, GR; Blednov, YA; Mayfield, R D; Harris, R A (Addiction Biology, 2019)
Chronic alcohol consumption alters the levels of microRNAs and mRNAs in the brain, but the specific microRNAs and processes that target mRNAs to affect cellular function and behavior are not known. We examined the in vivo manipulation of previously identified alcohol-responsive microRNAs as potential targets to reduce alcohol consumption. Silencing of miR-411 by infusing antagomiR-411 into the prefrontal cortex of female C57BL/6J mice reduced alcohol consumption and preference, without altering total fluid consumption, saccharin consumption, or anxiety-related behaviors. AntagomiR-411 reduced alcohol consumption when given to mice exposed to a chronic alcohol drinking paradigm but did not affect the acquisition of consumption in mice without a history of alcohol exposure, suggesting that antagomiR-411 has a neuroadaptive, alcohol-dependent effect. AntagomiR-411 decreased the levels of miR-411, as well as the association of immunoprecipitated miR-411 with Argonaute2; and, it increased levels of Faah and Ppard mRNAs. Moreover, antagomiR-411 increased the neuronal expression of glutamate receptor AMPA-2 protein, a known alcohol target and a predicted target of miR-411. These results suggest that alcohol and miR-411 function in a homeostatic manner to regulate synaptic mRNA and protein, thus reversing alcohol-related neuroadaptations and reducing chronic alcohol consumption.

Silencing synaptic MicroRNA‐411 reduces voluntary alcohol consumption in mice - Most D,; Salem NA,; Tiwari GR,; Blednov YA,; Mayfield RD; Harris RA (Addiction Biology, 2019)
Chronic alcohol consumption alters the levels of microRNAs and mRNAs in the brain, but the specific microRNAs and processes that target mRNAs to affect cellular function and behavior are not known. We examined the in vivo manipulation of previously identified alcohol‐responsive microRNAs as potential targets to reduce alcohol consumption. Silencing of miR‐411 by infusing antagomiR‐411 into the prefrontal cortex of female C57BL/6J mice reduced alcohol consumption and preference, without altering total fluid consumption, saccharin consumption, or anxiety‐related behaviors. AntagomiR‐411 reduced alcohol consumption when given to mice exposed to a chronic alcohol drinking paradigm but did not affect the acquisition of consumption in mice without a history of alcohol exposure, suggesting that antagomiR‐411 has a neuroadaptive, alcohol‐dependent effect. AntagomiR‐411 decreased the levels of miR‐411, as well as the association of immunoprecipitated miR‐411 with Argonaute2; and, it increased levels of Faah and Ppard mRNAs. Moreover, antagomiR‐411 increased the neuronal expression of glutamate receptor AMPA‐2 protein, a known alcohol target and a predicted target of miR‐411. These results suggest that alcohol and miR‐411 function in a homeostatic manner to regulate synaptic mRNA and protein, thus reversing alcohol‐related neuroadaptations and reducing chronic alcohol consumption.

Synaptic adaptations in the central amygdala and hypothalamic paraventricular nucleus associated with protracted ethanol abstinence in male rhesus monkeys - Jimenez VA,; Herman MA,; Cuzon Carlson VC,; Walter NA,; Grant KA,; Roberto M (Neuropsychopharmacology, 2019)
Alcohol use disorder is a significant global burden. Stress has been identified as an etiological factor in the initiation and continuation of ethanol consumption. Understanding adaptations within stress circuitry is an important step toward novel treatment strategies. The effects of protracted abstinence following long-term ethanol self-administration on the central nucleus of the amygdala (CeA) and the hypothalamic paraventricular nucleus (PVN) were evaluated in male rhesus monkeys. Using whole-cell patch-clamp electrophysiology, inhibitory GABAergic transmission in the CeA and excitatory glutamatergic transmission in the PVN were measured. CeA neurons from abstinent drinkers displayed an elevated baseline spontaneous inhibitory postsynaptic current (sIPSC) frequency compared with controls, indicating increased presynaptic GABA release. Application of acute ethanol significantly increased the frequency of sIPSCs in controls, but not in abstinent drinkers, suggesting a tolerance to ethanol-enhanced GABA release in abstinent rhesus monkeys with a history of chronic ethanol self-administration and repeated abstinence. In the PVN, the frequency of spontaneous excitatory postsynaptic currents (sEPSC) was elevated in abstinent drinkers compared with controls, indicating increased presynaptic glutamate release. Notably, acute ethanol decreased presynaptic glutamate release onto parvocellular PVN neurons in both controls and abstinent drinkers, suggesting a lack of tolerance to acute ethanol among PVN neurons. These results are the first to demonstrate distinct synaptic adaptations and ethanol sensitivity in both the extrahypothalamic and hypothalamic stress circuits in abstinent rhesus males. Importantly, our findings describe adaptations in stress circuitry present in the brain at a state during abstinence, just prior to relapse to ethanol drinking.

Synaptic adaptations in the central amygdala and hypothalamic paraventricular nucleus associated with protracted ethanol abstinence in male rhesus monkeys - Jimenez VA,; Herman MA,; Cuzon Carlson VC,; Walter NA,; Grant KA,; Roberto, M (Neuropsychopharmacology, 2019)
Alcohol use disorder is a significant global burden. Stress has been identified as an etiological factor in the initiation and continuation of ethanol consumption. Understanding adaptations within stress circuitry is an important step toward novel treatment strategies. The effects of protracted abstinence following long-term ethanol self-administration on the central nucleus of the amygdala (CeA) and the hypothalamic paraventricular nucleus (PVN) were evaluated in male rhesus monkeys. Using whole-cell patch-clamp electrophysiology, inhibitory GABAergic transmission in the CeA and excitatory glutamatergic transmission in the PVN were measured. CeA neurons from abstinent drinkers displayed an elevated baseline spontaneous inhibitory postsynaptic current (sIPSC) frequency compared with controls, indicating increased presynaptic GABA release. Application of acute ethanol significantly increased the frequency of sIPSCs in controls, but not in abstinent drinkers, suggesting a tolerance to ethanol-enhanced GABA release in abstinent rhesus monkeys with a history of chronic ethanol self-administration and repeated abstinence. In the PVN, the frequency of spontaneous excitatory postsynaptic currents (sEPSC) was elevated in abstinent drinkers compared with controls, indicating increased presynaptic glutamate release. Notably, acute ethanol decreased presynaptic glutamate release onto parvocellular PVN neurons in both controls and abstinent drinkers, suggesting a lack of tolerance to acute ethanol among PVN neurons. These results are the first to demonstrate distinct synaptic adaptations and ethanol sensitivity in both the extrahypothalamic and hypothalamic stress circuits in abstinent rhesus males. Importantly, our findings describe adaptations in stress circuitry present in the brain at a state during abstinence, just prior to relapse to ethanol drinking.

Synaptic adaptations in the central amygdala and hypothalamic paraventricular nucleus associated with protracted ethanol abstinence in male rhesus monkeys. - Jimenez, VA; Herman, MA; Cuzon Carlson, VC; Walter, NA; Grant, KA; Roberto, M (Neuropsychopharmacology, 2019)
Alcohol use disorder is a significant global burden. Stress has been identified as an etiological factor in the initiation and continuation of ethanol consumption. Understanding adaptations within stress circuitry is an important step toward novel treatment strategies. The effects of protracted abstinence following long-term ethanol self-administration on the central nucleus of the amygdala (CeA) and the hypothalamic paraventricular nucleus (PVN) were evaluated in male rhesus monkeys. Using whole-cell patch-clamp electrophysiology, inhibitory GABAergic transmission in the CeA and excitatory glutamatergic transmission in the PVN were measured. CeA neurons from abstinent drinkers displayed an elevated baseline spontaneous inhibitory postsynaptic current (sIPSC) frequency compared with controls, indicating increased presynaptic GABA release. Application of acute ethanol significantly increased the frequency of sIPSCs in controls, but not in abstinent drinkers, suggesting a tolerance to ethanol-enhanced GABA release in abstinent rhesus monkeys with a history of chronic ethanol self-administration and repeated abstinence. In the PVN, the frequency of spontaneous excitatory postsynaptic currents (sEPSC) was elevated in abstinent drinkers compared with controls, indicating increased presynaptic glutamate release. Notably, acute ethanol decreased presynaptic glutamate release onto parvocellular PVN neurons in both controls and abstinent drinkers, suggesting a lack of tolerance to acute ethanol among PVN neurons. These results are the first to demonstrate distinct synaptic adaptations and ethanol sensitivity in both the extrahypothalamic and hypothalamic stress circuits in abstinent rhesus males. Importantly, our findings describe adaptations in stress circuitry present in the brain at a state during abstinence, just prior to relapse to ethanol drinking.

Toll-like receptor 3 activation increases voluntary alcohol intake in C57BL/6J male mice - Warden AS,; Azzam M,; Da Costa A,; Mason S,; Blednov YA,; Messing RO,; Mayfield RD; Harris RA (Brain Behavior and Immunity, 2019)
Many genes differentially expressed in brain tissue from human alcoholics and animals that have consumed large amounts of alcohol are components of the innate immune toll-like receptor (TLR) pathway. TLRs initiate inflammatory responses via two branches: (1) MyD88-dependent or (2) TRIF-dependent. All TLRs signal through MyD88 except TLR3. Prior work demonstrated a direct role for MyD88-dependent signaling in regulation of alcohol consumption. However, the role of TLR3 as a potential regulator of excessive alcohol drinking has not previously been investigated. To test the possibility TLR3 activation regulates alcohol consumption, we injected mice with the TLR3 agonist polyinosinic:polycytidylic acid (poly(I:C)) and tested alcohol consumption in an every-other-day two-bottle choice test. Poly(I:C) produced a persistent increase in alcohol intake that developed over several days. Repeated poly(I:C) and ethanol exposure altered innate immune transcript abundance; increased levels of TRIF-dependent pathway components correlated with increased alcohol consumption. Administration of poly(I:C) before exposure to alcohol did not alter alcohol intake, suggesting that poly(I:C) and ethanol must be present together to change drinking behavior. To determine which branch of TLR signaling mediates poly(I:C)-induced changes in drinking behavior, we tested either mice lacking MyD88 or mice administered a TLR3/dsRNA complex inhibitor. MyD88 null mutants showed poly(I:C)-induced increases in alcohol intake. In contrast, mice pretreated with a TLR3/dsRNA complex inhibitor reduced their alcohol intake, suggesting poly(I:C)-induced escalations in alcohol intake are, at least partially, dependent on TLR3. Together, these results strongly suggest that TLR3-dependent signaling drives excessive alcohol drinking behavior.

Toll-like receptor 3 activation increases voluntary alcohol intake in C57BL/6J male mice - Warden, AS; Azzam, M; Da Costa, A; Mason, S; Blednov, YA; Messing, RO; Mayfield, R D; Harris, R A (Brain Behavior and Immunity, 2019)
Many genes differentially expressed in brain tissue from human alcoholics and animals that have consumed large amounts of alcohol are components of the innate immune toll-like receptor (TLR) pathway. TLRs initiate inflammatory responses via two branches: (1) MyD88-dependent or (2) TRIF-dependent. All TLRs signal through MyD88 except TLR3. Prior work demonstrated a direct role for MyD88-dependent signaling in regulation of alcohol consumption. However, the role of TLR3 as a potential regulator of excessive alcohol drinking has not previously been investigated. To test the possibility TLR3 activation regulates alcohol consumption, we injected mice with the TLR3 agonist polyinosinic:polycytidylic acid (poly(I:C)) and tested alcohol consumption in an every-other-day two-bottle choice test. Poly(I:C) produced a persistent increase in alcohol intake that developed over several days. Repeated poly(I:C) and ethanol exposure altered innate immune transcript abundance; increased levels of TRIF-dependent pathway components correlated with increased alcohol consumption. Administration of poly(I:C) before exposure to alcohol did not alter alcohol intake, suggesting that poly(I:C) and ethanol must be present together to change drinking behavior. To determine which branch of TLR signaling mediates poly(I:C)-induced changes in drinking behavior, we tested either mice lacking MyD88 or mice administered a TLR3/dsRNA complex inhibitor. MyD88 null mutants showed poly(I:C)-induced increases in alcohol intake. In contrast, mice pretreated with a TLR3/dsRNA complex inhibitor reduced their alcohol intake, suggesting poly(I:C)-induced escalations in alcohol intake are, at least partially, dependent on TLR3. Together, these results strongly suggest that TLR3-dependent signaling drives excessive alcohol drinking behavior.

Toll-like receptor 3 dynamics in female C57BL/6J mice: Regulation of alcohol intake - Warden AS,; Azzam M,; Da Costa A,; Mason S,; Blednov YA,; Messing RO,; Mayfield RD; Harris RA (Brain Behavior and Immunity, 2019)
Although there are sex differences in the effects of alcohol on immune responses, it is unclear if sex differences in immune response can influence drinking behavior. Activation of toll-like receptor 3 (TLR3) by polyinosinic:polycytidylic acid (poly(I:C)) produced a rapid proinflammatory response in males that increased alcohol intake over time (Warden et al., 2019). Poly(I:C) produced a delayed and prolonged innate immune response in females. We hypothesized that the timecourse of innate immune activation could regulate drinking behavior in females. Therefore, we chose to test the effect of two time points in the innate immune activation timecourse on every-other-day two-bottle-choice drinking: (1) peak activation; (2) descending limb of activation. Poly(I:C) reduced ethanol consumption when alcohol access occurred during peak activation. Poly(I:C) did not change ethanol consumption when alcohol access occurred on the descending limb of activation. Decreased levels of MyD88-dependent pathway correlated with decreased alcohol intake and increased levels of TRIF-dependent pathway correlated with increased alcohol intake in females. To validate the effects of poly(I:C) were mediated through MyD88, we tested female mice lacking Myd88. Poly(I:C) did not change alcohol intake in Myd88 knockouts, indicating that poly(I:C)-induced changes in alcohol intake are dependent on MyD88 in females. We next determined if the innate immune timecourse also regulated drinking behavior in males. Poly(I:C) reduced ethanol consumption in males when alcohol was presented at peak activation. Therefore, the timecourse of innate immune activation regulates drinking behavior and sex-specific dynamics of innate immune response must be considered when designing therapeutics to treat excessive drinking.

Toll-like receptor 3 dynamics in female C57BL/6J mice: regulation of alcohol intake - Warden, AS; Azzam, M; Da Costa, A; Mason, S; Blednov, YA; Messing, RO; Mayfield, R D; Harris, R A (Brain Behavior and Immunity, 2019)
Although there are sex differences in the effects of alcohol on immune responses, it is unclear if sex differences in immune response can influence drinking behavior. Activation of toll-like receptor 3 (TLR3) by polyinosinic:polycytidylic acid (poly(I:C)) produced a rapid proinflammatory response in males that increased alcohol intake over time (Warden et al., 2019). Poly(I:C) produced a delayed and prolonged innate immune response in females. We hypothesized that the timecourse of innate immune activation could regulate drinking behavior in females. Therefore, we chose to test the effect of two time points in the innate immune activation timecourse on every-other-day two-bottle-choice drinking: (1) peak activation; (2) descending limb of activation. Poly(I:C) reduced ethanol consumption when alcohol access occurred during peak activation. Poly(I:C) did not change ethanol consumption when alcohol access occurred on the descending limb of activation. Decreased levels of MyD88-dependent pathway correlated with decreased alcohol intake and increased levels of TRIF-dependent pathway correlated with increased alcohol intake in females. To validate the effects of poly(I:C) were mediated through MyD88, we tested female mice lacking Myd88. Poly(I:C) did not change alcohol intake in Myd88 knockouts, indicating that poly(I:C)-induced changes in alcohol intake are dependent on MyD88 in females. We next determined if the innate immune timecourse also regulated drinking behavior in males. Poly(I:C) reduced ethanol consumption in males when alcohol was presented at peak activation. Therefore, the timecourse of innate immune activation regulates drinking behavior and sex-specific dynamics of innate immune response must be considered when designing therapeutics to treat excessive drinking

What Is addiction? How can animal and human research be used to advance research, diagnosis, and treatment of alcohol and other substance use disorders? - Bickel, WK; Crabbe, JC; Sher, KJ. (Alcoholism: Clinical and Experimental Research, 2019)
The current article highlights key issues in defining, studying, and treating addiction, a concept related to but distinct from substance use disorders. The discussion is based upon a roundtable discussion at the 2017 annual meeting of the Research Society on Alcoholism where Warren K. Bickel and John C. Crabbe were charged with answering a range of questions posed by Kenneth J. Sher. All the presenters highlighted a number of central concerns for those interested in assessing and treating addiction as well as those seeking to conduct basic preclinical research that is amenable to meaningful translation to the human condition. In addition, the discussion illustrated both the power and limitations of using any single theory to explain multiple phenomena subsumed under the rubric of addiction. Among the major issues examined were the important differences between traditional diagnostic approaches and current concepts of addiction, the difficulty of modeling key aspects of human addiction in nonhuman animals, key aspects of addiction that have, to date, received little empirical attention, and the importance of thinking of recovery as a phenomenon that possibly involves processes distinct from those undergirding the development and maintenance of addiction.

What Is Addiction? How Can Animal and Human Research Be Used to Advance Research, Diagnosis, and Treatment of Alcohol and Other Substance Use Disorders? - Bickel WK,; Crabbe JC,; Sher KJ (Alcoholism: Clinical and Experimental Research, 2019)
The current article highlights key issues in defining, studying, and treating addiction, a concept related to but distinct from substance use disorders. The discussion is based upon a roundtable discussion at the 2017 annual meeting of the Research Society on Alcoholism where Warren K. Bickel and John C. Crabbe were charged with answering a range of questions posed by Kenneth J. Sher. All the presenters highlighted a number of central concerns for those interested in assessing and treating addiction as well as those seeking to conduct basic preclinical research that is amenable to meaningful translation to the human condition. In addition, the discussion illustrated both the power and limitations of using any single theory to explain multiple phenomena subsumed under the rubric of addiction. Among the major issues examined were the important differences between traditional diagnostic approaches and current concepts of addiction, the difficulty of modeling key aspects of human addiction in nonhuman animals, key aspects of addiction that have, to date, received little empirical attention, and the importance of thinking of recovery as a phenomenon that possibly involves processes distinct from those undergirding the development and maintenance of addiction.

Apremilast alters behavioral responses to ethanol in mice: I. Reduced consumption and preference - Blednov, YA; Da Costa, AJ; Tarbox, T; Ponomareva, O; Messing, RO; Harris, R A (Alcoholism: Clinical and Experimental Research, 2018)
BACKGROUND: Phosphodiesterase type 4 (PDE4) inhibitors produce widespread anti-inflammatory effects and reduce ethanol (EtOH) consumption in several rodent models. These drugs are potential treatments for several diseases, including central nervous system disorders, but clinical use is limited by their emetic activity. Apremilast is a selective PDE4 inhibitor with fewer gastrointestinal side effects that is FDA-approved for the treatment of psoriasis. METHODS: We measured the acute and chronic effects of apremilast on EtOH consumption in male and female C57BL/6J mice using the continuous and intermittent 24-hour 2-bottle choice drinking models. We also studied the effects of apremilast on preference for sucrose or saccharin, spontaneous locomotor activity, and blood EtOH clearance. Finally, apremilast levels in plasma, liver, and brain were measured 1 or 2 hours after injection. RESULTS: In the continuous and intermittent drinking tests, apremilast (15 to 50 mg/kg, p.o.) dose dependently reduced EtOH intake and preference in male and female mice. Higher doses of apremilast (30 to 50 mg/kg) also reduced total fluid intake in these mice. Chronic administration of apremilast (20 mg/kg) produced a stable reduction in EtOH consumption in both drinking tests with no effect on total fluid intake. The drinking effects were reversible after drug treatment was replaced with vehicle administration (saline) for 2 to 4 days. Six daily apremilast injections did not alter preference for saccharin or sucrose in male or female mice. Apremilast (20 mg/kg) transiently decreased spontaneous locomotor activity and did not alter blood EtOH clearance. The highest levels of apremilast were found in liver followed by plasma and brain. CONCLUSIONS: Apremilast produced stable reductions in voluntary EtOH consumption and was rapidly distributed to plasma and tissues (including the brain), suggesting that it may be an improved PDE4 inhibitor for medication development and repurposing efforts to treat alcohol abuse. Copyright © 2018 by the Research Society on Alcoholism.

Apremilast alters behavioral responses to ethanol in mice: II. Increased sedation, intoxication, and reduced acute functional tolerance - Blednov, YA; Da Costa, AJ; Harris, R A; Messing, RO (Alcoholism: Clinical and Experimental Research, 2018)
BACKGROUND: In our companion paper, we reported that the phosphodiesterase type 4 inhibitor apremilast reduced ethanol (EtOH) intake and preference in different drinking models in male and female C57BL/6J mice. In this study, we measured the effects of apremilast on other behaviors that are correlated with EtOH consumption. METHODS: The effects of apremilast (20 mg/kg) on the following behaviors were studied in male and female C57BL/6J mice: locomotor response to a novel situation; EtOH- and lithium chloride (LiCl)-induced conditioned taste aversion (CTA) to saccharin; conditioned place preference (CPP) and conditioned place avoidance (CPA) to EtOH; severity of handling-induced convulsions after EtOH administration; EtOH-induced anxiolytic-like behavior in the elevated plus maze; duration of EtOH-induced loss of righting reflex (LORR); recovery from EtOH-induced motor impairment on the rotarod; and acute functional tolerance (AFT) to EtOH's ataxic effects. RESULTS: Apremilast did not change the acquisition of EtOH-induced CPP, severity of acute withdrawal from EtOH, or EtOH's anxiolytic-like effect. Apremilast did not alter the extinction of EtOH- or LiCl-induced CTA, but may interfere with acquisition of CTA to EtOH. Apremilast increased the acquisition of CPA to EtOH, reduced locomotor responses to a novel situation, and prolonged the duration of LORR and the recovery from acute motor incoordination induced by EtOH. The longer recovery from the ataxic effect may be attributed to reduced development of AFT to EtOH. CONCLUSIONS: Our results suggest that apremilast increases the duration of EtOH intoxication by reducing AFT. Apremilast also reduces some aspects of general reward and increases EtOH's aversive properties, which might also contribute to its ability to reduce EtOH drinking.

Astrocyte-specific transcriptome responses to chronic ethanol consumption. - Erickson, EK; Farris, SP; Blednov, YA; Mayfield, R D; Harris, R A (Pharmacogenomics Journal, 2018)
Astrocytes play critical roles in central nervous system (CNS) homeostasis and are implicated in the pathogenesis of neurological and psychiatric conditions, including drug dependence. Little is known about the effects of chronic ethanol consumption on astrocyte gene expression. To address this gap in knowledge, we performed transcriptome-wide RNA sequencing of astrocytes isolated from the prefrontal cortex (PFC) of mice following chronic ethanol consumption. Differential expression analysis revealed ethanol-induced changes unique to astrocytes that were not identified in total homogenate preparations. Astrocyte-specific gene expression revealed calcium-related signaling and regulation of extracellular matrix genes as responses to chronic ethanol use. These findings emphasize the importance of investigating expression changes in specific cellular populations to define molecular consequences of chronic ethanol consumption in mammalian brain.

(AZI2)3'UTR Is a new SLC6A3 downregulator associated with an epistatic protection against substance use disorders - Liu, K; Yu, J; Zhao, J; Zhou, Y; Xiong, N; Xu, J.; Wang, T; Bell, RL; Qing, H; Lin, Z (Molecular Neurobiology, 2018)
Regulated activity of SLC6A3, which encodes the human dopamine transporter (DAT), contributes to diseases such as substance abuse disorders (SUDs); however, the exact transcription mechanism remains poorly understood. Here, we used a common genetic variant of the gene, intron 1 DNP1B sequence, as bait to screen and clone a new transcriptional activity, AZI23'UTR, for SLC6A3. AZI23'UTR is a 3' untranslated region (3'UTR) of the human 5-Azacytidine Induced 2 gene (AZI2) but appeared to be transcribed independently of AZI2. Found to be present in both human cell nuclei and dopamine neurons, this RNA was shown to downregulate promoter activity through a variant-dependent mechanism in vitro. Both reduced RNA density ratio of AZI23'UTR/AZI2 and increased DAT mRNA levels were found in ethanol-naive alcohol-preferring rats. Secondary analysis of dbGaP GWAS datasets (Genome-Wide Association Studies based on the database of Genotypes and Phenotypes) revealed significant interactions between regions upstream of AZI23'UTR and SLC6A3 in SUDs. Jointly, our data suggest that AZI23'UTR confers variant-dependent transcriptional regulation of SLC6A3, a potential risk factor for SUDs.

CB(1) and ethanol effects on glutamatergic transmission in the central amygdala of male and female msP and Wistar rats - Kirson, D; Oleata, CS; Parsons, LH; Ciccocioppo, R; Roberto, M (Addiction Biology, 2018)
The central amygdala (CeA) is involved in the processing of anxiety and stress and plays a role in ethanol consumption. Chronic ethanol recruits stress systems in the CeA, leading to aversive withdrawal symptoms. Although primarily GABAergic, CeA contains glutamatergic afferents, and we have reported inhibitory effects of ethanol on locally evoked glutamatergic responses in CeA of Wistar and Marchigian Sardinian alcohol-preferring (msP) rats. Notably, msP rats display enhanced anxiety, stress and alcohol drinking, simulating the alcohol-dependent phenotype. Endocannabinoids are also involved in regulation of stress, and we previously demonstrated that cannabinoid receptor type 1 (CB1 ) activation decreases CeA GABAergic signaling and blocks ethanol enhancement of GABAergic signaling. Here, we sought to investigate the effects of CB1 activation (WIN 55,212-2; Win) and antagonism (AM251) with and without acute ethanol on glutamatergic synapses in CeA of female and male Wistar and msP rats. Using intracellular sharp pipette electrophysiology, we examined the effects of CB1 compounds on locally evoked excitatory postsynaptic potentials (EPSPs) in CeA and compared effects between strains, gender and estrous cycle. Acute ethanol decreased EPSP amplitudes in Wistars, and in male but not female msPs. Win decreased EPSP amplitudes in msPs, and in male but not female Wistars. Combined application of Win and ethanol resulted in strain-specific effects in female rats. We found no tonic CB1 signaling at glutamatergic synapses in CeA of any groups, and no interaction with ethanol. Collectively, these observations demonstrate sex-strain-specific differences in ethanol and endocannabinoid effects on CeA glutamatergic signaling.

Chronic ethanol consumption: role of TLR3/TRIF-dependent signaling - McCarthy, GM; Warden, AS; Bridges, CR; Blednov, YA; Harris, R A (Addiction Biology, 2018)
Chronic ethanol consumption stimulates neuroimmune signaling in the brain, and Toll-like receptor (TLR) activation plays a key role in ethanol-induced inflammation. However, it is unknown which of the TLR signaling pathways, the myeloid differentiation primary response gene 88 (MyD88) dependent or the TIR-domain-containing adapter-inducing interferon-β (TRIF) dependent, is activated in response to chronic ethanol. We used voluntary (every-other-day) chronic ethanol consumption in adult C57BL/6J mice and measured expression of TLRs and their signaling molecules immediately following consumption and 24 hours after removing alcohol. We focused on the prefrontal cortex where neuroimmune changes are the most robust and also investigated the nucleus accumbens and amygdala. Tlr mRNA and components of the TRIF-dependent pathway (mRNA and protein) were increased in the prefrontal cortex 24 hours after ethanol and Cxcl10 expression increased 0 hour after ethanol. Expression of Tlr3 and TRIF-related components increased in the nucleus accumbens, but slightly decreased in the amygdala. In addition, we demonstrate that the IKKε/TBK1 inhibitor Amlexanox decreases immune activation of TRIF-dependent pathway in the brain and reduces ethanol consumption, suggesting the TRIF-dependent pathway regulates drinking. Our results support the importance of TLR3 and the TRIF-dependent pathway in ethanol-induced neuroimmune signaling and suggest that this pathway could be a target in the treatment of alcohol use disorders.

Cis-acting allele specific expression (ASE) differences induced by alcohol and impacted by sex as well as parental genotype of origin. - Lo, CL; Lumeng, L; Bell, RL; Liang, T; Lossie, AC; Muir, WM; Zhou, FC (Alcohol Clin Exp, 2018)
BACKGROUND: Alcohol use disorders (AUDs) are influenced by complex interactions between the genetics of the individual and their environment. We have previously identified hundreds of polygenic genetic variants between the selectively bred high- and low-alcohol drinking (HAD and LAD) rat lines. Here, we report allele-specific expression (ASE) differences, between the HAD2 and LAD2 rat lines. METHODS: The HAD2 and LAD2 rats, which have been sequenced, were reciprocally crossed to generate 10 litters of F1 progeny. For 5 of these litters, the sire was HAD2, and for the other 5 litters, the sire was a LAD2. From these 10 litters, 2 males and 2 females were picked from each F1 litter (N = 40 total). The F1 pups were divided, balancing for sex and direction of cross, into an alcohol (15%) versus a water control group. Alcohol drinking started in the middle of adolescence (~postnatal day 35) and lasted 9 weeks. At the end of these treatments, rats were euthanized, the nucleus accumbens was dissected, and RNA was processed for RNA-sequencing and ASE analyses. RESULTS: Analyses revealed that adolescent ethanol (EtOH) drinking, individual EtOH drinking levels, parentage, and sex-of-animal affected ASEs of about 300 genes. The identified genes included those associated with EtOH metabolism (e.g., Aldh2); neuromodulatory function (e.g., Cckbr, Slc6a7, and Slc1a1); ion channel activity (e.g., Kcnc3); and other synaptic and epigenetic functions. CONCLUSIONS: These data indicate that EtOH drinking differentially amplified paternal versus maternal allelic contribution to the transcriptome. We hypothesize that this was due, at least in part, to EtOH-induced changes in cis-regulation of polymorphisms previously identified between the HAD2 and LAD2 rat lines. This report highlights the complexity of gene-by-environment interactions mediating a genetic predisposition for, and/or the active development of, AUDs.

The control of reward seeking - Darcq, E; Kieffer, BL (Biological Psychiatry, 2018)

Cross-species molecular dissection across alcohol behavioral domains. - Farris SP,; Riley BP,; Williams RW,; Mulligan MK,; Miles MF,; Lopez MF,; Hitzemann R,; Iancu OD,; Colville A,; Walter NAR,; Oberbeck DL,; Darakjian P,; et al. (Alcohol, 2018)
This review summarizes the proceedings of a symposium presented at the "Alcoholism and Stress: A Framework for Future Treatment Strategies" conference held in Volterra, Italy on May 9-12, 2017. Psychiatric diseases, including alcohol-use disorders (AUDs), are influenced through complex interactions of genes, neurobiological pathways, and environmental influences. A better understanding of the common neurobiological mechanisms underlying an AUD necessitates an integrative approach, involving a systematic assessment of diverse species and phenotype measures. As part of the World Congress on Stress and Alcoholism, this symposium provided a detailed account of current strategies to identify mechanisms underlying the development and progression of AUDs. Dr. Sean Farris discussed the integration and organization of transcriptome and postmortem human brain data to identify brain regional- and cell type-specific differences related to excessive alcohol consumption that are conserved across species. Dr. Brien Riley presented the results of a genome-wide association study of DSM-IV alcohol dependence; although replication of genetic associations with alcohol phenotypes in humans remains challenging, model organism studies show that COL6A3, KLF12, and RYR3 affect behavioral responses to ethanol, and provide substantial evidence for their role in human alcohol-related traits. Dr. Rob Williams expanded upon the systematic characterization of extensive genetic-genomic resources for quantifying and clarifying phenotypes across species that are relevant to precision medicine in human disease. The symposium concluded with Dr. Robert Hitzemann's description of transcriptome studies in a mouse model selectively bred for high alcohol ("binge-like") consumption and a non-human primate model of long-term alcohol consumption. Together, the different components of this session provided an overview of systems-based approaches that are pioneering the experimental prioritization and validation of novel genes and gene networks linked with a range of behavioral phenotypes associated with stress and AUDs.

Deformation-based morphometry MRI reveals brain structural modifications in living mu opioid receptor knockout mice. - Nasseef MT,; Devenyi GA; Mechling AE,; Harsan LA,; Chakravarty MM; Kieffer BL,; Darcq E, (Frontiers in Psychiatry, 2018)
Mu opioid receptor (MOR) activation facilitates reward processing and reduces pain, and brain networks underlying these effects are under intense investigation. Mice lacking the MOR gene (MOR KO mice) show lower drug and social reward, enhanced pain sensitivity and altered emotional responses. Our previous neuroimaging analysis using Resting-state (Rs) functional Magnetic Resonance Imaging (fMRI) showed significant alterations of functional connectivity (FC) within reward/aversion networks in these mice, in agreement with their behavioral deficits. Here we further used a structural MRI approach to determine whether volumetric alterations also occur in MOR KO mice. We acquired anatomical images using a 7-Tesla MRI scanner and measured deformation-based morphometry (DBM) for each voxel in subjects from MOR KO and control groups. Our analysis shows marked anatomical differences in mutant animals. We observed both local volumetric contraction (striatum, nucleus accumbens, bed nucleus of the stria terminalis, hippocampus, hypothalamus and periacqueducal gray) and expansion (prefrontal cortex, amygdala, habenula, and periacqueducal gray) at voxel level. Volumetric modifications occurred mainly in MOR-enriched regions and across reward/aversion centers, consistent with our prior FC findings. Specifically, several regions with volume differences corresponded to components showing highest FC changes in our previous Rs-fMRI study, suggesting a possible function-structure relationship in MOR KO-related brain differences. In conclusion, both Rs-fMRI and volumetric MRI in live MOR KO mice concur to disclose functional and structural whole-brain level mechanisms that likely drive MOR-controlled behaviors in animals, and may translate to MOR-associated endophenotypes or disease in humans.

Discovery of a potent, selective, and brain-penetrant small molecule that activates the orphan receptor GPR88 and reduces alcohol intake. - Jin, C; Decker, AM; Makhijani, VH; Besheer, J; Darcq, E; Kieffer, BL; Maitra, R (Journal of Medicinal Chemistry, 2018)
The orphan G-protein-coupled receptor GPR88 is highly expressed in the striatum. Studies using GPR88 knockout mice have suggested that the receptor is implicated in alcohol seeking and drinking behaviors. To date, the biological effects of GPR88 activation are still unknown due to the lack of a potent and selective agonist appropriate for in vivo investigation. In this study, we report the discovery of the first potent, selective, and brain-penetrant GPR88 agonist RTI-13951-33 (6). RTI-13951-33 exhibited an EC50 of 25 nM in an in vitro cAMP functional assay and had no significant off-target activity at 38 GPCRs, ion channels, and neurotransmitter transporters that were tested. RTI-13951-33 displayed enhanced aqueous solubility compared to (1 R,2 R)-2-PCCA (2) and had favorable pharmacokinetic properties for behavioral assessment. Finally, RTI-13951-33 significantly reduced alcohol self-administration and alcohol intake in a dose-dependent manner without effects on locomotion and sucrose self-administration in rats when administered intraperitoneally.

Effects of the nicotinic agonist varenicline, nicotinic antagonist r-bPiDI, and DAT inhibitor (R)-modafinil on co-use of ethanol and nicotine in female P rats - Maggio, SE; Saunders, MA; Baxter, TA; Nixon, K; Prendergast, MA; Zheng, G; Crooks, P; Dwoskinm, LP; Slack, RD; Newman, AH; Bell, RL; Bardo, MT (Psychopharmacology, 2018)
RATIONALE: Co-users of alcohol and nicotine are the largest group of polysubstance users worldwide. Commonalities in mechanisms of action for ethanol (EtOH) and nicotine proposes the possibility of developing a single pharmacotherapeutic to treat co-use. OBJECTIVES: Toward developing a preclinical model of co-use, female alcohol-preferring (P) rats were trained for voluntary EtOH drinking and i.v. nicotine self-administration in three phases: (1) EtOH alone (0 vs. 15%, two-bottle choice), (2) nicotine alone (0.03 mg/kg/infusion, active vs. inactive lever), and (3) concurrent access to both EtOH and nicotine. Using this model, we examined the effects of (1) varenicline, a nicotinic acetylcholine receptor (nAChR) partial agonist with high affinity for the α4β2* subtype; (2) r-bPiDI, a subtype-selective antagonist at α6β2* nAChRs; and (3) (R)-modafinil, an atypical inhibitor of the dopamine transporter (DAT). RESULTS: In phases 1 and 2, pharmacologically relevant intake of EtOH and nicotine was achieved. In the concurrent access phase (phase 3), EtOH consumption decreased while nicotine intake increased relative to phases 1 and 2. For drug pretreatments, in the EtOH access phase (phase 1), (R)-modafinil (100 mg/kg) decreased EtOH consumption, with no effect on water consumption. In the concurrent access phase, varenicline (3 mg/kg), r-bPiDI (20 mg/kg), and (R)-modafinil (100 mg/kg) decreased nicotine self-administration but did not alter EtOH consumption, water consumption, or inactive lever pressing. CONCLUSIONS: These results indicate that therapeutics which may be useful for smoking cessation via selective inhibition of α4β2* or α6β2* nAChRs, or DAT inhibition, may not be sufficient to treat EtOH and nicotine co-use.

Effects of withdrawal from chronic intermittent ethanol exposure on sleep characteristics of female and male mice - Huitron-Resendiz, S; Nadav, T; Krause, S; Cates-Gatto, C; Polis, I; Roberts, AJ (Alcoholism: Clinical and Experimental Research, 2018)
BACKGROUND: Sleep disruptions are an important consequence of alcohol use disorders. There is a dearth of preclinical studies examining sex differences in sleep patterns associated with ethanol (EtOH) dependence despite documented sex differences in alcohol-related behaviors and withdrawal symptoms. The purpose of this study was to investigate the effects of chronic intermittent EtOH on sleep characteristics in female and male mice. METHODS: Female and male C57BL6/J mice had access to EtOH/water 2-bottle choice (2BC) 2 h/d for 3 weeks followed by exposure to EtOH vapor (vapor-2BC) or air for 5 cycles of 4 days. An additional group never experienced EtOH (naïve). Mice were implanted with electroencephalographic (EEG) electrodes, and vigilance states were recorded across 24 hours on the fourth day of withdrawal. The amounts of wakefulness, slow-wave sleep (SWS), and rapid eye movement sleep were calculated, and spectral analysis was performed by fast Fourier transformation. RESULTS: Overall, vapor-2BC mice showed a decrease in the amount of SWS 4 days into withdrawal as well as a decrease in the power density of slow waves, indicating disruptions in both the amount and quality of sleep in EtOH-dependent mice. This was associated with a decrease in duration and an increase in number of SWS episodes in males and an increase in latency to sleep in females. CONCLUSIONS: Our results revealed overall deficits in sleep regulation in EtOH-dependent mice of both sexes. Female mice appeared to be more affected with regard to the triggering of sleep, while male mice appeared more sensitive to disruptions in the maintenance of sleep.

Estradiol enhances ethanol reward in female mice through activation of ERα and ERβ - Hilderbrand, ER; Lasek, AW (Hormones and Behavior, 2018)
Alcohol use disorder (AUD) manifests differently in men and women, but little is known about sex differences in the brain's response to ethanol. It is known that the steroid hormone 17β-estradiol (E2) regulates voluntary ethanol consumption in female rodents. However, the role of E2 as a regulator of ethanol reward has not been investigated. In this study, we tested for the effects of E2 and agonists selective for the classical estrogen receptors, ERα and ERβ, on ethanol reward in ovariectomized (OVX) mice using the conditioned place preference (CPP) test. E2 enhanced ethanol CPP and, while specific activation of either receptor alone had no effect, co-activation of ERα and ERβ also enhanced ethanol CPP, suggesting that E2 enhances ethanol reward in female mice through actions at both ERα and ERβ. These results have implications for sex differences in the development of AUD, suggesting that women may find ethanol more rewarding than men because of higher circulating E2 levels.

Ethanol acts on KCNK13 potassium channels in the ventral tegmental area to increase firing rate and modulate binge-like drinking. - You, C; Savarese, A; Vandegrift, BJ; He, D; Pandey, SC; Lasek, AW; Brodie, MS (Neuropharmacology, 2018)
Alcohol excitation of the ventral tegmental area (VTA) is important in neurobiological processes related to the development of alcoholism. The ionotropic receptors on VTA neurons that mediate ethanol-induced excitation have not been identified. Quinidine blocks ethanol excitation of VTA neurons, and blockade of two-pore potassium channels is among the actions of quinidine. Therefore two-pore potassium channels in the VTA may be potential targets for the action of ethanol. Here, we explored whether ethanol activation of VTA neurons is mediated by the two-pore potassium channel KCNK13. Extracellular recordings of the response of VTA neurons to ethanol were performed in combination with knockdown of Kcnk13 using a short hairpin RNA (shRNA) in C57BL/6 J mice. Real-time PCR and immunohistochemistry were used to examine expression of this channel in the VTA. Finally, the role of KCNK13 in binge-like drinking was examined in the drinking in the dark test after knockdown of the channel. Kcnk13 expression in the VTA was increased by acute ethanol exposure. Ethanol-induced excitation of VTA neurons was selectively reduced by shRNA targeting Kcnk13. Importantly, knockdown of Kcnk13 in the VTA resulted in increased alcohol drinking. These results are consistent with the idea that ethanol stimulates VTA neurons at least in part by inhibiting KCNK13, a specific two-pore potassium channel, and that KCNK13 can control both VTA neuronal activity and binge drinking. KCNK13 is a novel alcohol-sensitive molecular target and may be amenable to the development of pharmacotherapies for alcoholism treatment.

Ethanol and a rapid-acting antidepressant produce overlapping changes in exon expression in the synaptic transcriptome - Wolfe SA,; Farris SP,; Mayfield JE,; Heaney CF,; Erickson EK,; Harris RA; Mayfield RD; Raab-Graham KF (Neuropharmacology, 2018)
Alcohol use disorder (AUD) and major depressive disorder (MDD) are prevalent, debilitating, and highly comorbid disorders. The molecular changes that underlie their comorbidity are beginning to emerge. For example, recent evidence showed that acute ethanol exposure produces rapid antidepressant-like biochemical and behavioral responses. Both ethanol and fast-acting antidepressants block N-methyl-D-aspartate receptor (NMDAR) activity, leading to synaptic changes and long-lasting antidepressant-like behavioral effects. We used RNA sequencing to analyze changes in the synaptic transcriptome after acute treatment with ethanol or the NMDAR antagonist, Ro 25-6981. Ethanol and Ro 25-6981 induced differential, independent changes in gene expression. In contrast with gene-level expression, ethanol and Ro 25-6981 produced overlapping changes in exons, as measured by analysis of differentially expressed exons (DEEs). A prominent overlap in genes with DEEs indicated that changes in exon usage were important for both ethanol and Ro 25-6981 action. Structural modeling provided evidence that ethanol-induced exon expression in the NMDAR1 amino-terminal domain could induce conformational changes and thus alter NMDAR function. These findings suggest that the rapid antidepressant effects of ethanol and NMDAR antagonists reported previously may depend on synaptic exon usage rather than gene expression.

Ethanol modulates glutamatergic transmission and NMDAR-mediated synaptic plasticity in the agranular insular cortex. - Shillinglaw, JE; Morrisett, RA; Mangieri, RA (Frontiers in Pharmacology, 2018)
The agranular insular cortex (AIC) has recently been investigated by the alcohol field because of its connectivity to and modulatory control over limbic and brainstem regions implicated in alcohol use disorder (AUD), and because it has shown involvement in animal models of alcohol drinking. Despite evidence of AIC involvement in AUD, there has not yet been an examination of whether ethanol modulatesglutamatergic and γ-amino-butyric acid (GABA)ergic synaptic transmission and plasticity in the AIC. Characterizing how the synaptictransmission and plasticity states of AIC cortical processing neurons are modulated by acute ethanol will likely reveal the molecular targets by which chronic ethanol alters AIC function as alcohol drinking transitions from controlled to problematic. Therefore, we collected brain slices from ethanol-naïve adult male mice, obtained whole-cell recording configuration in layer 2/3 AIC pyramidal neurons, and bath-applied ethanolat pharmacologically relevant concentrations during electrophysiological assays of glutamatergic and GABAergic synaptic transmission and plasticity. We found that ethanol inhibited electrically evoked N-methyl-D-aspartate receptor (NMDAR)-mediated excitatory post-synapticcurrents (EPSCs) in a concentration-related fashion, and had little effect on evoked α-amino-3-hydrox-5-methylisoxazole-4-propionic acid-type receptor (AMPAR)-mediated EPSCs. Ethanol had no effect on spontaneous excitatory post-synaptic currents (sEPSCs) or inhibitory GABAAR-mediated post-synaptic currents (sIPSCs). We found that synaptic conditioning (low-frequency stimulation for 15 min at 1 Hz) induced a form of long-term depression (LTD) of evoked AMPAR-mediated EPSCs. The ability to induce LTD was inhibited by a non-selective NMDAR antagonist (DL-2-amino-5-phosphonovaleric acid), and also by acute, intoxicating concentrations of ethanol. Taken together these data suggest that the glutamate, but not GABA system in the AIC is uniquely sensitive to ethanol, and that in particular NMDAR-mediatedprocesses in the AIC may be disrupted by pharmacologically relevant concentrations of ethanol.

From gene networks to drugs: systems pharmacology approaches for AUD - Ferguson, LB; Harris, R A; Mayfield, R D (Psychopharmacology, 2018)
The alcohol research field has amassed an impressive number of gene expression datasets spanning key brain areas for addiction, species (humans as well as multiple animal models), and stages in the addiction cycle (binge/intoxication, withdrawal/negative effect, and preoccupation/anticipation). These data have improved our understanding of the molecular adaptations that eventually lead to dysregulation of brain function and the chronic, relapsing disorder of addiction. Identification of new medications to treat alcohol use disorder (AUD) will likely benefit from the integration of genetic, genomic, and behavioral information included in these important datasets. Systems pharmacology considers drug effects as the outcome of the complex network of interactions a drug has rather than a single drug-molecule interaction. Computational strategies based on this principle that integrate gene expression signatures of pharmaceuticals and disease states have shown promise for identifying treatments that ameliorate disease symptoms (called in silico gene mapping or connectivity mapping). In this review, we suggest that gene expression profiling for in silico mapping is critical to improve drug repurposing and discovery for AUD and other psychiatric illnesses. We highlight studies that successfully apply gene mapping computational approaches to identify or repurpose pharmaceutical treatments for psychiatric illnesses. Furthermore, we address important challenges that must be overcome to maximize the potential of these strategies to translate to the clinic and improve healthcare outcomes.

Gender specific effects of selection for drinking in the dark on the network roles of coding and non-coding RNAs. - Iancu, OD; Colville, A; Wilmot, B; Searles, R; Darakjian, P; Zheng, C; McWeeney, S; Kawane, S; Crabbe, JC; Metten, P; Oberbeck, D; Hitzemann, R (Alcohol Clin Exp, 2018)
BACKGROUND: Transcriptional differences between heterogeneous stock mice and high drinking-in-the-dark selected mouse lines have previously been described based on microarray technology coupled with network-based analysis. The network changes were reproducible in 2 independent selections and largely confined to 2 distinct network modules; in contrast, differential expression appeared more specific to each selected line. This study extends these results by utilizing RNA-Seq technology, allowing evaluation of the relationship between genetic risk and transcription of noncoding RNA (ncRNA); we additionally evaluate sex-specific transcriptional effects of selection. METHODS: Naïve mice (N = 24/group and sex) were utilized for gene expression analysis in the ventral striatum; the transcriptome was sequenced with the Illumina HiSeq platform. Differential gene expression and the weighted gene co-expression network analysis were implemented largely as described elsewhere, resulting in the identification of genes that change expression level or (co)variance structure. RESULTS: Across both sexes, we detect selection effects on the extracellular matrix and synaptic signaling, although the identity of individual genes varies. A majority of nc RNAs cluster in a single module of relatively low density in both the male and female network. The most strongly differentially expressed transcript in both sexes was Gm22513, a small nuclear RNA with unknown function. Associated with selection, we also found a number of network hubs that change edge strength and connectivity. At the individual gene level, there are many sex-specific effects; however, at the annotation level, results are more concordant. CONCLUSIONS: In addition to demonstrating sex-specific effects of selection on the transcriptome, the data point to the involvement of extracellular matrix genes as being associated with the binge drinking phenotype.

Genome-wide expression profiles drive discovery of novel compounds that reduce binge drinking in mice - Ferguson, LB; Ozburn, AR; Ponomarev, I; Metten, P; Reilly, M; Crabbe, JC; Harris, R A; Mayfield RD (Neuropharmacology, 2018)
Transcriptome-based drug discovery has identified new treatments for some complex diseases, but has not been applied to alcohol use disorder (AUD) or other psychiatric diseases, where there is a critical need for improved pharmacotherapies. High Drinking in the Dark (HDID-1) mice are a genetic model of AUD risk that have been selectively bred (from the HS/Npt line) to achieve intoxicating blood alcohol levels (BALs) after binge-like drinking. We compared brain gene expression of HDID-1 and HS/Npt mice, to determine a molecular signature for genetic risk for high intensity, binge-like drinking. Using multiple computational methods, we queried LINCS-L1000 (Library of Integrated Network-Based Cellular Signatures), a database containing gene expression signatures of thousands of compounds, to predict candidate drugs with the greatest potential to decrease alcohol consumption. Our analyses predicted novel compounds for testing, many with anti-inflammatory properties, providing further support for a neuroimmune mechanism of excessive alcohol drinking. We validated the top 2 candidates in vivo as a proof-of-concept. Terreic acid (a Bruton's tyrosine kinase inhibitor) and pergolide (a dopamine and serotonin receptor agonist) robustly reduced alcohol intake and BALs in HDID-1 mice, providing the first evidence for transcriptome-based drug discovery to target an addiction trait. Effective drug treatments for many psychiatric diseases are lacking, and the emerging tools and approaches outlined here offer researchers studying complex diseases renewed opportunities to discover new or repurpose existing compounds and expedite treatment options.

Heavy chronic intermittent ethanol exposure alters small noncoding RNAs in mouse sperm and epididymosomes - Rompala, GR; Mounier, A; Wolfe, CM; Lin, Q; Lefterov, I; Homanics, GE (Frontiers in Genetics, 2018)
While the risks of maternal alcohol abuse during pregnancy are well-established, several preclinical studies suggest that chronic preconception alcohol consumption by either parent may also have significance consequences for offspring health and development. Notably, since isogenic male mice used in these studies are not involved in gestation or rearing of offspring, the cross-generational effects of paternal alcohol exposure suggest a germline-based epigenetic mechanism. Many recent studies have demonstrated that the effects of paternal environmental exposures such as stress or malnutrition can be transmitted to the next generation via alterations to small noncoding RNAs in sperm. Therefore, we used high throughput sequencing to examine the effect of preconception ethanol on small noncoding RNAs in sperm. We found that chronic intermittent ethanol exposure altered several small noncoding RNAs from three of the major small RNA classes in sperm, tRNA-derived small RNA (tDR), mitochondrial small RNA, and microRNA. Six of the ethanol-responsive small noncoding RNAs were evaluated with RT-qPCR on a separate cohort of mice and five of the six were confirmed to be altered by chronic ethanol exposure, supporting the validity of the sequencing results. In addition to altered sperm RNA abundance, chronic ethanol exposure affected post-transcriptional modifications to sperm small noncoding RNAs, increasing two nucleoside modifications previously identified in mitochondrial tRNA. Furthermore, we found that chronic ethanol reduced epididymal expression of a tRNA methyltransferase, Nsun2, known to directly regulate tDR biogenesis. Finally, ethanol-responsive sperm tDR are similarly altered in extracellular vesicles of the epididymis (i.e., epididymosomes), supporting the hypothesis that alterations to sperm tDR emerge in the epididymis and that epididymosomes are the primary source of small noncoding RNAs in sperm. These results add chronic ethanol to the growing list of paternal exposures that can affect small noncoding RNA abundance and nucleoside modifications in sperm. As small noncoding RNAs in sperm have been shown to causally induce heritable phenotypes in offspring, additional research is warranted to understand the potential effects of ethanol-responsive sperm small noncoding RNAs on offspring health and development.

An improved model of ethanol and nicotine co-use in female P rats: effects of naltrexone, varenicline, and the selective nicotinic α6β2* antagonist r-bPiDI. - Maggio, SE; Saunders, MA; Nixon, K; Prendergast, MA; Zheng, G; Crooks, PA; Dwoskin, LP; Bell, RL; Bardo, MT (Drug and Alcohol Dependence, 2018)
Background Although pharmacotherapies are available for alcohol (EtOH) or tobacco use disorders individually, it may be possible to develop a single pharmacotherapy to treat heavy drinking tobacco smokers by capitalizing on the commonalities in their mechanisms of action. Methods Female alcohol-preferring (P) rats were trained for EtOH drinking and nicotine self-administration in two phases: (1) EtOH alone (0 vs. 15% EtOH, 2-bottle choice) and (2) concomitant access, during which EtOH access continued with access to nicotine (0.03 mg/kg/infusion, i.v.) using a 2-lever choice procedure (active vs. inactive lever) in which the fixed ratio (FR) requirement was gradually increased to FR30. When stable co-use was obtained, rats were pretreated with varying doses of naltrexone, varenicline, or r-bPiDI, an α6β2* subtype-selective nicotinic acetylcholine receptor antagonist shown previously to reduce nicotine self-administration. Results While EtOH intake was initially suppressed in phase 2 (co-use), pharmacologically relevant intake for both substances was achieved by raising the "price" of nicotine to FR30. In phase 2, naltrexone decreased EtOH and water consumption but not nicotine intake; in contrast, naltrexone in phase 1 (EtOH only) did not significantly alter EtOH intake. Varenicline and r-bPiDI in phase 2 both decreased nicotine self-administration and inactive lever pressing, but neither altered EtOH or water consumption. Conclusions These results indicate that increasing the "price" of nicotine increases EtOH intake during co-use. Additionally, the efficacy of naltrexone, varenicline, and r-bPiDI was specific to either EtOH or nicotine, with no efficacy for co-use. Nevertheless, future studies on combining these treatments may reveal synergistic efficacy.

Increased alcohol seeking in mice lacking Gpr88 involves dysfunctional mesocorticolimbic networks. - Ben Hamida S,; Mendonça-Netto S,; Arefin TM,; Nasseef MT,; Boulos LJ,; McNicholas M,; Ehrlich AT,; Clarke E,; Moquin L,; Gratton A,; Darcq E,; Harsan LA, (Biological Psychiatry, 2018)
BACKGOUND: Alcohol use disorder (AUD) is devastating and poorly treated, and innovative targets are actively sought for prevention and treatment. The orphan G protein-coupled receptor GPR88 is enriched in mesocorticolimbic pathways, and Gpr88 knockout mice show hyperactivity and risk-taking behavior, but a potential role for this receptor in drug abuse has not been examined. METHODS: We tested Gpr88 knockout mice for alcohol-drinking and -seeking behaviors. To gain system-level understanding of their alcoholendophenotype, we also analyzed whole-brain functional connectivity in naïve mice using resting-state functional magnetic resonance imaging. RESULTS: Gpr88 knockout mice showed increased voluntary alcohol drinking at both moderate and excessive levels, with intact alcoholsedation and metabolism. Mutant mice also showed increased operant responding and motivation for alcohol, while food and chocolate operant self-administration were unchanged. Alcohol place conditioning and alcohol-induced dopamine release in the nucleus accumbens were decreased, suggesting reduced alcohol reward in mutant mice that may partly explain enhanced alcohol drinking. Seed-based voxelwise functional connectivity analysis revealed significant remodeling of mesocorticolimbic centers, whose hallmark was predominant weakening of prefrontal cortex, ventral tegmental area, and amygdala connectional patterns. Also, effective connectivity from the ventral tegmental area to the nucleus accumbens and amygdala was reduced. CONCLUSIONS: Gpr88 deletion disrupts executive, reward, and emotional networks in a configuration that reduces alcohol reward and promotes alcohol seeking and drinking. The functional connectivity signature is reminiscent of alterations observed in individuals at risk for AUD. The Gpr88 gene, therefore, may represent a vulnerability/resilience factor for AUD, and a potential drug target for AUD treatment.

Jacobian maps reveal under-reported brain regions sensitive to extreme binge ethanol intoxication in the rat. - Zhao, Q; Fritz, M; Pfefferbaum A,; Sullivan, EV; Pohl, KM; Zahr, NM (Frontiers in Neuroanatomy, 2018)
Individuals aged 12-20 years drink 11% of all alcohol consumed in the United States with more than 90% consumed in the form of bingedrinking. Early onset alcohol use is a strong predictor of future alcohol dependence. The study of the effects of excessive alcohol use on the human brain is hampered by limited information regarding the quantity and frequency of exposure to alcohol. Animal models can control for age at alcohol exposure onset and enable isolation of neural substrates of exposure to different patterns and quantities of ethanol (EtOH). As with humans, a frequently used binge exposure model is thought to produce dependence and affect predominantly corticolimbic brainregions. in vivo neuroimaging enables animals models to be examined longitudinally, allowing for each animal to serve as its own control. Accordingly, we conducted 3 magnetic resonance imaging (MRI) sessions (baseline, binge, recovery) to track structure throughout the brains of wild type Wistar rats to test the hypothesis that binge EtOH exposure affects specific brain regions in addition to corticolimbic circuitry. Voxel-based comparisons of 13 EtOH- vs. 12 water- exposed animals identified significant thalamic shrinkage and lateral ventricular enlargement as occurring with EtOH exposure, but recovering with a week of abstinence. By contrast, pretectal nuclei and superior and inferior colliculi shrank in response to binge EtOH treatment but did not recover with abstinence. These results identify brainstem structures that have been relatively underreported but are relevant for localizing neurocircuitry relevant to the dynamic course of alcoholism.

. Long-term ethanol exposure: temporal pattern of microRNA expression and associated mRNA gene networks in mouse brain - Osterndorff-Kahanek, EA; Tiwari, GR; Lopez, MF; Becker, HC; Harris, R A; Mayfield, R D (PLoS One, 2018)
Long-term alcohol use can result in lasting changes in brain function, ultimately leading to alcohol dependence. These functional alterations arise from dysregulation of complex gene networks, and growing evidence implicates microRNAs as key regulators of these networks. We examined time- and brain region-dependent changes in microRNA expression after chronic intermittent ethanol (CIE) exposure in C57BL/6J mice. Animals were sacrificed at 0, 8, and 120h following the last exposure to four weekly cycles of CIE vapor and we measured microRNA expression in prefrontal cortex (PFC), nucleus accumbens (NAC), and amygdala (AMY). The number of detected (395–419) and differentially expressed (DE, 42–47) microRNAs was similar within each brain region. However, the DE microRNAs were distinct among brain regions and across time within each brain region. DE microRNAs were linked with their DE mRNA targets across each brain region. In all brain regions, the greatest number of DE mRNA targets occurred at the 0 or 8h time points and these changes were associated with microRNAs DE at 0 or 8h. Two separate approaches (discrete temporal association and hierarchical clustering) were combined with pathway analysis to further characterize the temporal relationships between DE microRNAs and their 120h DE targets. We focused on targets dysregulated at 120h as this time point represents a state of protracted withdrawal known to promote an increase in subsequent ethanol consumption. Discrete temporal association analysis identified networks with highly connected genes including ERK1/2 (mouse equivalent Mapk3, Mapk1), Bcl2 (in AMY networks) and Srf (in PFC networks). Similarly, the cluster-based analysis identified hub genes that include Bcl2 (in AMY networks) and Srf in PFC networks, demonstrating robust microRNA-mRNA network alterations in response to CIE exposure. In contrast, datasets utilizing targets from 0 and 8h microRNAs identified NF-kB-centered networks (in NAC and PFC), and Smad3-centered networks (in AMY). These results demonstrate that CIE exposure results in dynamic and complex temporal changes in microRNA-mRNA gene network structure.

Long-term subregion-specific encoding of enhanced ethanol intake by D1DR medium spiny neurons of the nucleus accumbens - Renteria, R; Buske, TR; Morrisett, RA (Addiction Biology, 2018)
While the risks of maternal alcohol abuse during pregnancy are well-established, several preclinical studies suggest that chronic preconception alcohol consumption by either parent may also have significance consequences for offspring health and development. Notably, since isogenic male mice used in these studies are not involved in gestation or rearing of offspring, the cross-generational effects of paternal alcohol exposure suggest a germline-based epigenetic mechanism. Many recent studies have demonstrated that the effects of paternal environmental exposures such as stress or malnutrition can be transmitted to the next generation via alterations to small noncoding RNAs in sperm. Therefore, we used high throughput sequencing to examine the effect of preconception ethanol on small noncoding RNAs in sperm. We found that chronic intermittent ethanol exposure altered several small noncoding RNAs from three of the major small RNA classes in sperm, tRNA-derived small RNA (tDR), mitochondrial small RNA, and microRNA. Six of the ethanol-responsive small noncoding RNAs were evaluated with RT-qPCR on a separate cohort of mice and five of the six were confirmed to be altered by chronic ethanol exposure, supporting the validity of the sequencing results. In addition to altered sperm RNA abundance, chronic ethanol exposure affected post-transcriptional modifications to sperm small noncoding RNAs, increasing two nucleoside modifications previously identified in mitochondrial tRNA. Furthermore, we found that chronic ethanol reduced epididymal expression of a tRNA methyltransferase, Nsun2, known to directly regulate tDR biogenesis. Finally, ethanol-responsive sperm tDR are similarly altered in extracellular vesicles of the epididymis (i.e., epididymosomes), supporting the hypothesis that alterations to sperm tDR emerge in the epididymis and that epididymosomes are the primary source of small noncoding RNAs in sperm. These results add chronic ethanol to the growing list of paternal exposures that can affect small noncoding RNA abundance and nucleoside modifications in sperm. As small noncoding RNAs in sperm have been shown to causally induce heritable phenotypes in offspring, additional research is warranted to understand the potential effects of ethanol-responsive sperm small noncoding RNAs on offspring health and development.

Microglial-specific transcriptome changes following chronic alcohol consumption. - McCarthy, GM; Farris, SP; Blednov, YA; Harris, R A; Mayfield, R D (Neuropharmacology, 2018)
Microglia are fundamentally important immune cells within the central nervous system (CNS) that respond to environmental challenges to maintain normal physiological processes. Alterations in steady-state cellular function and over-activation of microglia can facilitate the initiation and progression of neuropathological conditions such as Alzheimer's disease, Multiple Sclerosis, and Major Depressive Disorder. Alcohol consumption disrupts signaling pathways including both innate and adaptive immune responses that are necessary for CNS homeostasis. Coordinate expression of these genes is not ascertained from an admixture of CNS cell-types, underscoring the importance of examining isolated cellular populations to reveal systematic gene expression changes arising from mature microglia. Unbiased RNA-Seq profiling was used to identify gene expression changes in isolated prefrontal cortical microglia in response to recurring bouts of voluntary alcohol drinking behavior. The voluntary ethanol paradigm utilizes long-term consumption ethanol that results in escalated alcohol intake and altered cortical plasticity that is seen in humans. Gene coexpression analysis identified a coordinately regulated group of genes, unique to microglia, that collectively are associated with alcohol consumption. Genes within this group are involved in toll-like receptor signaling and transforming growth factor beta signaling. Network connectivity of this group identified Siglech as a putative hub gene and highlighted the potential importance of proteases in the microglial response to chronic ethanol. In conclusion, we identified a distinctive microglial gene expression signature for neuroimmune responses related to alcohol consumption that provides valuable insight into microglia-specific changes underlying the development of substance abuse, and possibly other CNS disorders.

A molecular mechanism for choosing alcohol over an alternative reward - Augier, E; Barbier, E; Dulman, RS; Licheri, V; Augier, G; Domi, E; Barchiesi, R; Farris, S; Nätt, D; Mayfield, R D; Adermark, L; Heilig, M (Science, 2018)
Alcohol addiction leads to increased choice of alcohol over healthy rewards. We established an exclusive choice procedure in which ~15% of outbred rats chose alcohol over a high-value reward. These animals displayed addiction-like traits, including high motivation to obtain alcoholand pursuit of this drug despite adverse consequences. Expression of the γ-aminobutyric acid (GABA) transporter GAT-3 was selectively decreased within the amygdala of alcohol-choosing rats, whereas a knockdown of this transcript reversed choice preference of rats that originally chose a sweet solution over alcohol. GAT-3 expression was selectively decreased in the central amygdala of alcohol-dependent people compared to those who died of unrelated causes. Impaired GABA clearance within the amygdala contributes to alcohol addiction, appears to translate between species, and may offer targets for new pharmacotherapies for treating this disorder.

Morphological and functional evidence of increased excitatory signaling in the prelimbic cortex during ethanol withdrawal - Varodayan, FP; Sidhu, H; Kreifeldt, M; Roberto, M; Contet, C (Neuropharmacology, 2018)
Excessive alcohol consumption in humans induces deficits in decision making and emotional processing, which indicates a dysfunction of the prefrontal cortex (PFC). The present study aimed to determine the impact of chronic intermittent ethanol (CIE) inhalation on mouse medial PFC pyramidal neurons. Data were collected 6–8 days into withdrawal from 7 weeks of CIE exposure, a time point when mice exhibit behavioral symptoms of withdrawal. We found that spine maturity in prelimbic (PL) layer 2/3 neurons was increased, while dendritic spines in PL layer 5 neurons or infralimbic (IL) neurons were not affected. Corroborating these morphological observations, CIE enhanced glutamatergic transmission in PL layer 2/3 pyramidal neurons, but not IL layer 2/3 neurons. Contrary to our predictions, these cellular alterations were associated with improved, rather than impaired, performance in reversal learning and strategy switching tasks in the Barnes maze at an earlier stage of chronic ethanol exposure (5–7 days withdrawal from 3 to 4 weeks of CIE), which could result from the anxiety-like behavior associated with ethanol withdrawal. Altogether, this study adds to a growing body of literature indicating that glutamatergic activity in the PFC is upregulated following chronic ethanol exposure, and identifies PL layer 2/3 pyramidal neurons as a sensitive target of synaptic remodeling. It also indicates that the Barnes maze is not suitable to detect deficits in cognitive flexibility in CIE-withdrawn mice.

Morphological and functional evidence of increased excitatory signaling in the prelimbic cortex during ethanol withdrawal. - Varodayan, FP; Sidhu, H; Kreifeldt, M; Roberto, M; Contet, C (Neuropharmacology, 2018)
Excessive alcohol consumption in humans induces deficits in decision making and emotional processing, which indicates a dysfunction of the prefrontal cortex (PFC). The present study aimed to determine the impact of chronic intermittent ethanol (CIE) inhalation on mouse medial PFC pyramidal neurons. Data were collected 6-8 days into withdrawal from 7 weeks of CIE exposure, a time point when mice exhibit behavioral symptoms of withdrawal. We found that spine maturity in prelimbic (PL) layer 2/3 neurons was increased, while dendritic spines in PL layer 5 neurons or infralimbic (IL) neurons were not affected. Corroborating these morphological observations, CIE enhanced glutamatergic transmission in PL layer 2/3 pyramidal neurons, but not IL layer 2/3 neurons. Contrary to our predictions, these cellular alterations were associated with improved, rather than impaired, performance in reversal learning and strategy switching tasks in the Barnes maze at an earlier stage of chronic ethanol exposure (5-7 days withdrawal from 3 to 4 weeks of CIE), which could result from the anxiety-like behavior associated with ethanol withdrawal. Altogether, this study adds to a growing body of literature indicating that glutamatergic activity in the PFC is upregulated following chronic ethanol exposure, and identifies PL layer 2/3 pyramidal neurons as a sensitive target of synaptic remodeling. It also indicates that the Barnes maze is not suitable to detect deficits in cognitive flexibility in CIE-withdrawn mice.

Novel small-molecule inhibitors of protein kinase C epsilon reduce ethanol consumption in mice. - Blasio A,; Wang J,; Wang D,; Varodayan FP; Pomrenze MB,; Miller J,; Lee AM,; McMahon T,; Gyawali S,; Wang HY,; Roberto M; McHardy S,; et al. (Biological Psychiatry, 2018)
BACKGROUND: Despite the high cost and widespread prevalence of alcohol use disorders, treatment options are limited, underscoring the need for new, effective medications. Previous results using protein kinase C epsilon (PKCε) knockout mice, RNA interference against PKCε, and peptide inhibitors of PKCε predict that small-molecule inhibitors of PKCε should reduce alcohol consumption in humans. METHODS: We designed a new class of PKCε inhibitors based on the Rho-associated protein kinase (ROCK) inhibitor Y-27632. In vitro kinase and binding assays were used to identify the most potent compounds. Their effects on ethanol-stimulated synaptic transmission; ethanol, sucrose, and quinine consumption; ethanol-induced loss of righting; and ethanol clearance were studied in mice. RESULTS: We identified two compounds that inhibited PKCε with Ki <20 nM, showed selectivity for PKCε over other kinases, crossed the blood-brain barrier, achieved effective concentrations in mouse brain, prevented ethanol-stimulated gamma-aminobutyric acid release in the central amygdala, and reduced ethanol consumption when administered intraperitoneally at 40 mg/kg in wild-type but not in Prkce-/- mice. One compound also reduced sucrose and saccharin consumption, while the other was selective for ethanol. Both transiently impaired locomotion through an off-target effect that did not interfere with their ability to reduce ethanol intake. One compound prolonged recovery from ethanol-induced loss of righting but this was also due to an off-target effect since it was present in Prkce-/- mice. Neither altered ethanolclearance. CONCLUSIONS: These results identify lead compounds for development of PKCε inhibitors that reduce alcohol consumption.

Opioid receptors: drivers to addiction? - Darcq E,; Kieffer BL, (Nature Reviews Neuroscience, 2018)
Drug addiction is a worldwide societal problem and public health burden, and results from recreational drug use that develops into a complex brain disorder. The opioid system, one of the first discovered neuropeptide systems in the history of neuroscience, is central to addiction. Recently, opioid receptors have been propelled back on stage by the rising opioid epidemics, revolutions in G protein-coupled receptor research and fascinating developments in basic neuroscience. This Review discusses rapidly advancing research into the role of opioid receptors in addiction, and addresses the key questions of whether we can kill pain without addiction using mu-opioid-receptor-targeting opiates, how mu- and kappa-opioid receptors operate within the neurocircuitry of addiction and whether we can bridge human and animal opioid research in the field of drug abuse.

Ovarian hormones contribute to high levels of binge-like drinking by female mice - Satta, R; Hilderbrand, ER; Lasek, AW (Alcoholism: Clinical and Experimental Research, 2018)
BACKGROUND: Recently, the incidence of binge drinking by women has increased. Binge drinking is detrimental to women's health, yet the biological mechanisms that promote excessive drinking by women are not well understood. One method of assessing binge-like ethanol (EtOH) consumption in mice is the drinking in the dark (DID) test, in which mice drink sufficient EtOH to achieve intoxication. In this study, we directly compared male, female, and ovariectomized (OVX) mice for DID and tested whether 17β-estradiol (E2) contributes to DID. We also measured whether DID varies throughout the estrous cycle and whether repeated intermittent DID impacts the estrous cycle. METHODS: Male, female, and OVX C57BL/6J mice were tested for DID for 2 hours per day on days 1 to 3 and for 4 hours on day 4 using a single bottle containing 20% EtOH. To measure the effects of E2 on DID, OVX mice were treated with estradiol benzoate (EB) or vehicle daily starting 2 weeks prior to the drinking test and throughout the DID procedure. In a separate group of experiments, EtOH consumption and estrous cycle phase were measured in freely cycling mice that were drinking EtOH or water 5 days per week for 2 or 6 weeks. RESULTS: Female mice consumed more EtOH than male and OVX mice. Treatment with EB increased EtOH consumption by OVX mice compared with vehicle-treated controls. However, EtOH intake did not vary across the estrous cycle, nor did long-term DID alter the estrous cycle. CONCLUSIONS: These results demonstrate that ovarian hormones, specifically E2, contribute to increased EtOH consumption by female mice in the DID test. Although ovarian hormones contribute to this behavior, EtOH consumption is not affected by estrous cycle phase in freely cycling mice. This study provides a framework for understanding the factors that contribute to binge drinking in females.

Paternal preconception chronic variable stress confers attenuated ethanol drinking behavior selectively to male offspring in a pre-stress environment dependent manner. - Rompala, GR; Simons, A; Kihle, B; Homanics, GE (Frontiers in Behavioral Neuroscience, 2018)
Stress-related psychiatric disorders such as major depression are strongly associated with alcohol abuse and alcohol use disorder. Recently, many epidemiological and preclinical studies suggest that chronic stress prior to conception has cross-generational effects on the behaviorand physiological response to stress in subsequent generations. Thus, we hypothesized that chronic stress may also affect ethanol drinkingbehaviors in the next generation. In the first cohort of mice, we found that paternal preconception chronic variable stress significantly reduced both two-bottle choice and binge-like ethanol drinking selectively in male offspring. However, these results were not replicated in a second cohort that were tested under experimental conditions that were nearly identical, except for one notable difference. Cohort 1 offspring were derived from in-house C57BL/6J sires that were born in the animal vivarium at the University of Pittsburgh whereas cohort 2 offspring were derived from C57BL/6J sires shipped directly from the vendor. Therefore, a third cohort that included both in-house and vendor born sires was analyzed. Consistent with the first two cohorts, we observed a significant interaction between chronic stress and sire-source with only stressed sires that were born in-house able to impart reduced ethanol drinking behaviors to male offspring. Overall, these results demonstrate that paternal preconception stress can impact ethanol drinking behavior in males of the next generation. These studies provide additional support for a recently recognized role of the paternal preconception environment in shaping ethanol drinking behavior.

Peri-adolescent drinking of ethanol and/or nicotine modulates astroglial glutamate transporters and metabotropic glutamate receptor-1 in female alcohol-preferring rats - Alasmari, F; Bell, RL; Rao, PSS; Hammad, AM; Sari, Y (Pharmacology Biochemistry and Behavior, 2018)
Impairment in glutamate neurotransmission mediates the development of dependence upon nicotine (NIC) and ethanol (EtOH). Previous work indicates that continuous access to EtOH or phasic exposure to NIC reduces expression of the glutamate transporter-1 (GLT-1) and cystine/glutamate antiporter (xCT) but not the glutamate/aspartate transporter (GLAST). Additionally, metabotropic glutamate receptors (mGluRs) expression was affected following exposure to EtOH or NIC. However, little is known about the effects of EtOH and NIC co-consumption on GLT-1, xCT, GLAST, and mGluR1 expression. In this study, peri-adolescent female alcohol preferring (P) rats were given binge-like access to water, sucrose (SUC), SUC-NIC, EtOH, or EtOH-NIC for four weeks. The present study determined the effects of these reinforcers on GLT-1, xCT, GLAST, and mGluR1 expression in the nucleus accumbens (NAc), hippocampus (HIP) and prefrontal cortex (PFC). GLT-1 and xCT expression were decreased in the NAc following both SUC-NIC and EtOH-NIC. In addition, only xCT expression was downregulated in the HIP in both of these latter groups. Also, glutathione peroxidase (GPx) activity in the HIP was reduced following SUC, SUC-NIC, EtOH, and EtOH-NIC consumption. Similar to previous work, GLAST expression was not altered in any brain region by any of the reinforcers. However, mGluR1 expression was increased in the NAc in the SUC-NIC, EtOH, and EtOH-NIC groups. These results indicate that peri-adolescent binge-like drinking of EtOH or SUC with or without NIC may exert differential effects on astroglial glutamate transporters and receptors. Our data further parallel some of the previous findings observed in adult rats.

Peroxisome proliferator activated receptor agonists modulate transposable element expression in brain and liver. - Ferguson, LB; Zhang, L; Wang, S; Bridges, C; Harris, R A; Ponomarev, I (Frontiers in Molecular Neuroscience, 2018)
Peroxisome proliferator activated receptors (PPARs) are nuclear hormone receptors that act as transcription factors in response to endogenous lipid messengers. The fibrates and thiazolidinediones are synthetic PPAR agonists used clinically to treat dyslipidemia and Type 2 Diabetes Mellitus, respectively, but also improve symptoms of several other diseases. Transposable elements (TEs), repetitive sequences in mammalian genomes, are implicated in many of the same conditions for which PPAR agonists are therapeutic, including neurodegeneration, schizophrenia, and drug addiction. We tested the hypothesis that there is a link between actions of PPAR agonists and TE expression. We developed an innovative application of microarray data by mapping Illumina mouse WG-6 microarray probes to areas of the mouse genome that contain TEs. Using this information, we assessed the effects of systemic administration of three PPAR agonists with different PPAR subtype selectivity: fenofibrate, tesaglitazar, and bezafibrate, on TE probe expression in mouse brain [prefrontal cortex (PFC) and amygdala] and liver. We found that fenofibrate, and bezafibrate to a lesser extent, up-regulated probes mapped to retrotransposons: Short-Interspersed Elements (SINEs) and Long-Interspersed Elements (LINEs), in the PFC. Conversely, all PPAR agonists down-regulated LINEs and tesaglitazar and bezafibrate also down-regulated SINEs in liver. We built gene coexpression networks that partitioned the diverse transcriptional response to PPAR agonists into groups of probes with highly correlated expression patterns (modules). Most of the differentially expressed retrotransposons were within the same module, suggesting coordinated regulation of their expression, possibly by PPAR signaling. One TE module was conserved across tissues and was enriched with genes whose products participate in epigenetic regulation, suggesting that PPAR agonists affect TE expression via epigenetic mechanisms. Other enriched functional categories included phenotypes related to embryonic development and learning and memory, suggesting functional links between these biological processes and TE expression. In summary, these findings suggest mechanistic relationships between retrotransposons and PPAR agonists and provide a basis for future exploration of their functional roles in brain and liver.

Persistence of drug memories: melting transcriptomes - Mayfield, R D; Harris, RA. (Biological Psychiatry, 2018)
One of the defining characteristics of drug dependence is relapse after a period of abstinence. Cue-induced drug craving and relapse risk not only persist during abstinence, but increase over time, a phenomenon termed incubation (1). This progressive increase in risk factors likely requires enduring “memory-like” changes in synaptic plasticity, but there has been little exploration of the underlying molecular mechanisms. It is assumed that this remodeling of the brain is initiated by changes in gene expression (2). The artwork by Salvador Dali titled The Disintegration of the Persistence of Memory offers a symbolic illustration of how extrinsic factors shape the transcriptome over time (<a data-ga-action="click_feat_suppl" href="https://www.wikiart.org/en/salvador-dali/the-disintegration-of-the-persistence-of-memory" ref="reftype=extlink&article-id=6338210&issue-id=327795&journal-id=319&FROM=Article%7CBody&TO=External%7CLink%7CURI" target="_blank">https://www.wikiart.org/en/salvador-dali/the-disintegration-of-the-persistence-of-memory). Viewed from this perspective, the bricks in the painting evoke the assembly of RNA sequencing reads into a transcriptome in a surrealist landscape that implies a relationship to memories and time, while the water simulates the depth of changes by drugs of abuse. These persistent influences produce a transcriptome melting pot.

Pharmacogenetic Manipulation of the Nucleus Accumbens Alters Binge-Like Alcohol Drinking in Mice - Purohit, K; Parekh, PK; Kern, J; Logan, RW; Liu, Z.; Huang, Y; McClung, CA; Crabbe, JC; Ozburn, AR (Alcoholism: Clinical and Experimental Research, 2018)
BACKGROUND: Chronic alcohol intake leads to long-lasting changes in reward- and stress-related neuronal circuitry. The nucleus accumbens (NAc) is an integral component of this circuitry. Here, we investigate the effects of DREADDs (Designer Receptors Exclusively Activated by Designer Drugs) on neuronal activity in the NAc and binge-like drinking. METHODS: C57BL/6J mice were stereotaxically injected with AAV2 hSyn-HA hM3Dq, -hM4Di, or -eGFP bilaterally into NAc [core + shell, core or shell]. We measured clozapine-n-oxide (CNO)-induced changes in NAc activity and assessed binge-like ethanol (EtOH) or tastant/fluid intake in a limited access Drinking in the Dark (DID) schedule. RESULTS: We found that CNO increased NAc firing in hM3Dq positive cells and decreased firing in hM4Di cells, confirming the efficacy of these channels to alter neuronal activity both spatially and temporally. Increasing NAc core + shell activity decreased binge-like drinking without altering intake of other tastants. Increasing activity specifically in the NAc core reduced binge-like drinking, and decreasing activity in the NAc core increased drinking. Manipulation of NAc shell activity did not alter DID. Thus, we find that increasing activity in the entire NAc, or just the NAc core is sufficient to decrease binge drinking. CONCLUSIONS: We conclude that the reduction in EtOH drinking is not due to general malaise, altered perception of taste, or reduced calorie-seeking. Furthermore, we provide the first evidence for bidirectional control of NAc core and binge-like drinking. These findings could have promising implications for treatment.

Pharmacological inhibition of receptor protein tyrosine phosphatase β/ζ (PTPRZ1) modulates behavioral responses to ethanol - Fernández-Calle, R; Vicente-Rodríguez, M; Pastor, M; Gramage, E; Di Geronimo, B; Zapico, JM; Coderch, C; Pérez-García, C; Lasek, AW; de Pascual-Teresa, B; Ramos, A; Herradón, G (Neuropharmacology, 2018)
Pleiotrophin (PTN) and Midkine (MK) are neurotrophic factors that are upregulated in the prefrontal cortex after alcohol administration and have been shown to reduce ethanol drinking and reward. PTN and MK are the endogenous inhibitors of Receptor Protein Tyrosine Phosphatase (RPTP) β/ζ (a.k.a. PTPRZ1, RPTPβ, PTPζ), suggesting a potential role for this phosphatase in the regulation of alcohol effects. To determine if RPTPβ/ζ regulates ethanol consumption, we treated mice with recently developed small-molecule inhibitors of RPTPβ/ζ (MY10, MY33-3) before testing them for binge-like drinking using the drinking in the dark protocol. Mice treated with RPTPβ/ζ inhibitors, particularly with MY10, drank less ethanol than controls. MY10 treatment blocked ethanol conditioned place preference, showed limited effects on ethanol-induced ataxia, and potentiated the sedative effects of ethanol. We also tested whether RPTPβ/ζ is involved in ethanol signaling pathways. We found that ethanol treatment of neuroblastoma cells increased phosphorylation of anaplastic lymphoma kinase (ALK) and TrkA, known substrates of RPTPβ/ζ. Treatment of neuroblastoma cells with MY10 or MY33-3 also increased levels of phosphorylated ALK and TrkA. However, concomitant treatment of neuroblastoma cells with ethanol and MY10 or MY33-3 prevented the increase in pTrkA and pALK. These results demonstrate for the first time that ethanol engages TrkA signaling and that RPTPβ/ζ modulates signaling pathways activated by alcohol and behavioral responses to this drug. The data support the hypothesis that RPTPβ/ζ might be a novel target of pharmacotherapy for reducing excessive alcohol consumption.

Regional differences and similarities in the brain transcriptome for mice selected for ethanol preference from HS-CC founders. - Colville, AM; Iancu, OD; Lockwood, DR; Darakjian, P; McWeeney, SK; Searles, R; Zheng, C; Hitzemann, R (2018)
The high genetic complexity found in heterogeneous stock (HS-CC) mice, together with selective breeding, can be used to detect new pathways and mechanisms associated with ethanol preference and excessive ethanol consumption. We predicted that these pathways would provide new targets for therapeutic manipulation. Previously (Colville et al., 2017), we observed that preference selection strongly affected the accumbens shell (SH) genes associated with synaptic function and in particular genes associated with synaptic tethering. Here we expand our analyses to include substantially larger sample sizes and samples from two additional components of the "addiction circuit," the central nucleus of the amygdala (CeA) and the prelimbic cortex (PL). At the level of differential expression (DE), the majority of affected genes are region-specific; only in the CeA did the DE genes show a significant enrichment in GO annotation categories, e.g., neuron part. In all three brain regions the differentially variable genes were significantly enriched in a single network module characterized by genes associated with cell-to-cell signaling. The data point to glutamate plasticity as being a key feature of selection for ethanol preference. In this context the expression of Dlg2 which encodes for PSD-93 appears to have a key role. It was also observed that the expression of the clustered protocadherins was strongly associated with preference selection.

Regulation of anxiety-like behavior and Crhr1 expression in the basolateral amygdala by LMO3. - Savarese A,; Lasek AW, (Psychoneuroendocrinology, 2018)
The LIM domain only protein LMO3 is a transcriptional regulator that has been shown to regulate several behavioral responses to alcohol. Specifically, Lmo3 null (Lmo3Z) mice consume more ethanol in a binge-drinking test and show enhanced ethanol-induced sedation. Due to the high comorbidity of alcohol use and anxiety, we investigated anxiety-like behavior in Lmo3Z mice. Lmo3Z mice spent more time in the open arms of the elevated plus maze compared with their wild-type littermates, but the effect was confounded by reduced locomotor activity. To verify the anxiety phenotype in the Lmo3Z mice, we tested them for novelty-induced hypophagia and found that they also showed reduced anxiety in this test. We next explored the mechanism by which LMO3 might regulate anxiety by measuring mRNA and protein levels of corticotropin releasing factor (encoded by the Crh gene) and its receptor type 1 (Crhr1) in Lmo3Z mice. Reduced Crhr1 mRNA and protein was evident in the basolateral amygdala (BLA) of Lmo3Z mice. To examine whether Lmo3 in the amygdala is important for anxiety-like behavior, we locally reduced Lmo3 expression in the BLA of wild type mice using a lentiviral vector expressing a short hairpin RNA targeting the Lmo3 transcript. Mice with Lmo3 knockdown in the BLA exhibited decreased anxiety-like behavior relative to control mice. These results suggest that Lmo3 promotes anxiety-like behavior specifically in the BLA, possibly by altering Crhr1 expression. This study is the first to support a role for Lmo3 in anxiety-like behavior.

On the relationships in rhesus macaques between chronic ethanol consumption and the brain transcriptome - Iancu, OD; Colville, A; Walter, NAR; Darakjian, P; Oberbeck, DL; Daunais, JB; Zheng, CL; Searles, RP; McWeeney, SK; Grant, KA; Hitzemann, R (Addiction Biology, 2018)
This is the first description of the relationship between chronic ethanol self-administration and the brain transcriptome in a non-human primate (rhesus macaque). Thirty-one male animals self-administered ethanol on a daily basis for over 12 months. Gene transcription was quantified with RNA-Seq in the central nucleus of the amygdala (CeA) and cortical Area 32. We constructed coexpression and cosplicing networks, and we identified areas of preservation and areas of differentiation between regions and network types. Correlations between intake and transcription included largely distinct gene sets and annotation categories across brain regions and between expression and splicing; positive and negative correlations were also associated with distinct annotation groups. Membrane, synaptic and splicing annotation categories were over-represented in the modules (gene clusters) enriched in positive correlations (CeA); our cosplicing analysis further identified the genes affected only at the exon inclusion level. In the CeA coexpression network, we identified Rab6b, Cdk18 and Igsf21 among the intake-correlated hubs, while in the Area 32, we identified a distinct hub set that included Ppp3r1 and Myeov2. Overall, the data illustrate that excessive ethanol self-administration is associated with broad expression and splicing mechanisms that involve membrane and synapse genes.

Releasing addiction memories trapped in perineuronal nets. - Lasek, AW; Chen, H; Chen, WY (Trends in Genetics, 2018)
Drug addiction can be conceptualized on a basic level as maladaptive learning and memory. Addictive substances elicit changes in brain circuitry involved in reward, cognition, and emotional state, leading to the formation and persistence of strong drug-associated memories that lead to craving and relapse. Recently, perineuronal nets (PNNs), extracellular matrix structures surrounding neurons, have emerged as regulators of learning, memory, and addiction behaviors. PNNs do not just provide structural support to neurons, but are dynamically remodeled in an experience-dependent manner by metalloproteinases. They function in various brain regions through constituent proteins such as brevican that are implicated in neural plasticity. Understanding the function of PNN components in memory processes may lead to new therapeutic approaches to treating addiction.

Role of TLR4 in the modulation of central amygdala GABA transmission by CRF following restraint stress. - Varodayan, FP; Khom, S; Patel, RR; Steinman MQ,; Hedges, DM; Oleata, CS; Homanics, GE; Roberto, M; Bajo, M. (Alcohol and Alcoholism, 2018)
AIMS: Stress induces neuroimmune responses via Toll-like receptor 4 (TLR4) activation. Here, we investigated the role of TLR4 in the effects of the stress peptide corticotropin-releasing factor (CRF) on GABAergic transmission in the central nucleus of the amygdala (CeA) followingrestraint stress. METHODS: Tlr4 knock out (KO) and wild-type rats were exposed to no stress (naïve), a single restraint stress (1 h) or repeated restraintstress (1 h per day for 3 consecutive days). After 1 h recovery from the final stress session, whole-cell patch-clamp electrophysiology was used to investigate the effects of CRF (200 nM) on CeA GABAA-mediated spontaneous inhibitory postsynaptic currents (sIPSCs). RESULTS: TLR4 does not regulate baseline GABAergic transmission in the CeA of naive and stress-treated animals. However, CRFsignificantly increased the mean sIPSC frequencies (indicating enhanced GABA release) across all genotypes and stress treatments, except for the Tlr4 KO rats that experienced repeated restraint stress. CONCLUSIONS: Overall, our results suggest a limited role for TLR4 in CRF's modulation of CeA GABAergic synapses in naïve and single stress rats, though TLR4-deficient rats that experienced repeated psychological stress exhibit a blunted CRF cellular response. SHORT SUMMARY: TLR4 has a limited role in CRF's activation of the CeA under basal conditions, but interacts with the CRF system to regulate GABAergic synapse function in animals that experience repeated psychological stress.

Selective breeding for high alcohol consumption and response to nicotine: locomotor activity, dopaminergic in the mesolimbic system, and innate genetic differences in male and female alcohol-preferring, non-preferring, and replicate lines of high-alcohol - Deehan, GA Jr; Hauser, SR; Getachew, B; Waeiss, RA; Engleman, EA; Knight, CP; McBride, WJ; Truitt, WA; Bell, RL; Rodd, ZA. (Psychopharmacology, 2018)
RATIONALE: There is evidence for a common genetic link between alcohol and nicotine dependence. Rodents selectively bred for high alcohol consumption/responsivity are also more likely to self-administer nicotine than controls. OBJECTIVES: The experiments examined the response to systemic nicotine, the effects of nicotine within the drug reward pathway, and innate expression of nicotine-related genes in a brain region regulating drug reward/self-administration in multiple lines of rats selectively bred for high and low alcohol consumption. METHODS: The experiments examined the effects of systemic administration of nicotine on locomotor activity, the effects of nicotineadministered directly into the (posterior ventral tegmental area; pVTA) on dopamine (DA) release in the nucleus accumbens shell (AcbSh), and innate mRNA levels of acetylcholine receptor genes in the pVTA were determined in 6 selectively bred high/low alcohol consuming and Wistar rat lines. RESULTS: The high alcohol-consuming rat lines had greater nicotine-induced locomotor activity compared to low alcohol-consuming rat lines. Microinjections of nicotine into the pVTA resulted in DA release in the AcbSh with the dose response curves for high alcohol-consuming ratsshifted leftward and upward. Genetic analysis of the pVTA indicated P rats expressed higher levels of α2 and β4. CONCLUSION: Selective breeding for high alcohol preference resulted in a genetically divergent behavioral and neurobiological sensitivity to nicotine. The observed behavioral and neurochemical differences between the rat lines would predict an increased likelihood of nicotinereinforcement. The data support the hypothesis of a common genetic basis for drug addiction and identifies potential receptor targets.

Studying sex differences in animal models of addiction: an emphasis on alcohol-related behaviors. - Hilderbrand, ER; Lasek, AW (ACS Chemical Neuroscience, 2018)
Animal models are essential for understanding the biological factors that contribute to drug and alcohol addiction and discovering new pharmacotherapies to treat these disorders. Alcohol (ethanol) is the most commonly abused drug in the world, and as the prevalence of alcohol use disorder (AUD) increases, so does the need for effective pharmacotherapies. In particular, treatments with high efficacy in the growing number of female AUD sufferers are needed. Female animals remain underrepresented in biomedical research and sex differencesin the brain's response to alcohol are poorly understood. To help bridge the gender gap in addiction research, this Review discusses strategies that researchers can use to examine sex differences in the context of several common animal models of AUD. Self-administration, two-bottle choice, drinking in the dark, and conditioned place preference are discussed, with a focus on the role of estrogen as a mediator of sex differences in alcohol-related behaviors.

Transcriptional regulators as targets for alcohol pharmacotherapies. - Savarese, AM; Lasek, AW (Handbook of Experimental Pharmacology, 2018)
Alcohol use disorder (AUD) is a chronic relapsing brain disease that currently afflicts over 15 million adults in the United States. Despite its prevalence, there are only three FDA-approved medications for AUD treatment, all of which show limited efficacy. Because of their ability to alter expression of a large number of genes, often with great cell-type and brain-region specificity, transcription factors and epigenetic modifiers serve as promising new targets for the development of AUD treatments aimed at the neural circuitry that underlies chronic alcoholabuse. In this chapter, we will discuss transcriptional regulators that can be targeted pharmacologically and have shown some efficacy in attenuating alcohol consumption when targeted. Specifically, the transcription factors cyclic AMP-responsive element binding protein (CREB), peroxisome proliferator-activated receptors (PPARs), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and glucocorticoid receptor (GR), as well as the epigenetic enzymes, the DNA methyltransferases (DNMTs) and histone deacetylases (HDACs), will be discussed.

11β-hydroxysteroid dehydrogenase inhibition as a new potential therapeutic target for alcohol abuse - Sanna, PP; Kawamura, T; Chen, J; Koob, GF; Roberts, AJ; Vendruscolo, LF; Repunte-Canonigo, V (Translational Psychiatry, 2017)
The identification of new and more effective treatments for alcohol abuse remains a priority. Alcohol intake activates glucocorticoids, which have a key role in alcohol's reinforcing properties. Glucocorticoid effects are modulated in part by the activity of 11β-hydroxysteroid dehydrogenases (11β-HSD) acting as pre-receptors. Here, we tested the effects on alcohol intake of the 11β-HSD inhibitor carbenoxolone (CBX, 18β-glycyrrhetinic acid 3β-O-hemisuccinate), which has been extensively used in the clinic for the treatment of gastritis and peptic ulcer and is active on both 11β-HSD1 and 11β-HSD2 isoforms. We observed that CBX reduces both baseline and excessive drinking in rats and mice. The CBX diastereomer 18α-glycyrrhetinic acid 3β-O-hemisuccinate (αCBX), which we found to be selective for 11β-HSD2, was also effective in reducing alcohol drinking in mice. Thus, 11β-HSD inhibitors may be a promising new class of candidate alcohol abuse medications, and existing 11β-HSD inhibitor drugs may be potentially re-purposed for alcohol abuse treatment.

Alcohol dependence disrupts amygdalar L-type voltage-gated calcium channel mechanisms - Varodayan, FP; de Guglielmo, G; Logrip, ML; George, O; Roberto, M (Journal of Neuroscience, 2017)
L-type voltage-gated calcium channels (LTCCs) are implicated in several psychiatric disorders that are comorbid with alcoholism and involve amygdala dysfunction. Within the amygdala, the central nucleus (CeA) is critical in acute alcohol's reinforcing actions, and its dysregulation in human alcoholics drives their negative emotional state and motivation to drink. Here we investigated the specific role of CeA LTCCs in the effects of acute alcohol at the molecular, cellular physiology, and behavioral levels, and their potential neuroadaptation in alcohol-dependent rats. Alcohol increases CeA activity (neuronal firing rates and GABA release) in naive rats by engaging LTCCs, and intra-CeA LTCC blockade reduces alcohol intake in nondependent rats. Alcohol dependence reduces CeA LTCC membrane abundance and disrupts this LTCC-based mechanism; instead, corticotropin-releasing factor type 1 receptors (CRF1s) mediate alcohol's effects on CeA activity and drive the escalated alcohol intake of alcohol-dependent rats. Collectively, our data indicate that alcohol dependence functionally alters the molecular mechanisms underlying the CeA's response to alcohol (from LTCC- to CRF1-driven). This mechanistic switch contributes to and reflects the prominent role of the CeA in the negative emotional state that drives excessive drinking.SIGNIFICANCE STATEMENT The central amygdala (CeA) plays a critical role in the development of alcohol dependence. As a result, much preclinical alcohol research aims to identify relevant CeA neuroadaptions that promote the transition to dependence. Here we report that acute alcohol increases CeA neuronal activity in naive rats by engaging L-type calcium channels (LTCCs) and that intra-CeA LTCC blockade reduces alcohol intake in nondependent rats. Alcohol dependence disrupts this LTCC-based mechanism; instead, corticotropin-releasing factor type 1 receptors (CRF1s) mediate alcohol's effects on CeA activity and drive the escalated alcohol intake of alcohol-dependent rats. This switch reflects the important role of the CeA in the pathophysiology of alcohol dependence and represents a new potential avenue for therapeutic intervention during the transition period.

An alcohol withdrawal test battery measuring multiple behavioral symptoms in mice - Metten, P; Schlumbohm, JP; Huang, LC; Greenberg, GD; Hack, WR; Spence, SE; Crabbe, JC (Alcohol, 2017)
Despite acceptance that risk for alcohol-use disorder (AUD) has a large genetic component, the identification of genes underlying various components of risk for AUD has been hampered in humans, in part by the heterogeneity of expression of the phenotype. One aspect of AUD is physical dependence. Alcohol withdrawal is a serious consequence of alcohol dependence with multiple symptoms, many of which are seen in multiple species, and can be experienced over a wide-ranging time course. In the present three studies, we developed a battery of withdrawal tests in mice, examining behavioral symptoms from multiple domains that could be measured over time. To permit eventual use of the battery in different strains of mice, we used male and female mice of a genetically heterogeneous stock developed from intercrossing eight inbred strains. Withdrawal symptoms were assessed using commonly used tests after administration of ethanol in vapor for 72 continuous hours. We found significant effects of ethanol withdrawal versus air-breathing controls on nearly all symptoms, spanning 4 days following ethanol vapor inhalation. Withdrawal produced hypothermia, greater neurohyperexcitability (seizures and tremor), anxiety-like behaviors using an apparatus (such as reduced transitions between light and dark compartments), anhedonia (reduced sucrose preference), Straub tail, backward walking, and reductions in activity; however, there were no changes in thermal pain sensitivity, hyper-reactivity to handling, or anxiety-like emergence behaviors in other apparatus. Using these data, we constructed a refined battery of withdrawal tests. Individual differences in severity of withdrawal among different tests were weakly correlated at best. This battery should be useful for identifying genetic influences on particular withdrawal behaviors, which should reflect the influences of different constellations of genes.

Alcohol's Effects on the Brain: Neuroimaging Results in Humans and Animal Models - Zahr, NM; Pfefferbaum, A; Sullivan, EV (Alchol Research, 2017)
Brain imaging technology has allowed researchers to conduct rigorous studies of the dynamic course of alcoholism through periods of drinking, sobriety, and relapse and to gain insights into the effects of chronic alcoholism on the human brain. Magnetic resonance imaging (MRI) studies have distinguished alcohol-related brain effects that are permanent from those that are reversible with abstinence. In support of postmortem neuropathological studies showing degeneration of white matter, MRI studies have shown a specific vulnerability of white matter to chronic alcohol exposure. Such studies have demonstrated white-matter volume deficits as well as damage to selective gray-matter structures. Diffusion tensor imaging (DTI), by permitting microstructural characterization of white matter, has extended MRI findings in alcoholics. MR spectroscopy (MRS) allows quantification of several metabolites that shed light on brain biochemical alterations caused by alcoholism. This article focuses on MRI, DTI, and MRS findings in neurological disorders that commonly co-occur with alcoholism, including Wernicke's encephalopathy, Korsakoff's syndrome, and hepatic encephalopathy. Also reviewed are neuroimaging findings in animal models of alcoholism and related neurological disorders. This report also suggests that the dynamic course of alcoholism presents a unique opportunity to examine brain structural and functional repair and recovery.

Alignment of the transcriptome with individual variation in animals selectively bred for High Drinking-In-the-Dark (HDID). - Hitzemann R,; Oberbeck D,; Iancu O,; Darakjian P,; McWeeney S,; Spence S,; Schlumbohm J,; Metten P,; Crabbe J, (Alcohol, 2017)
Among animals at risk for excessive ethanol consumption such as the HDID selected mouse lines, there is considerable individual variation in the amount of ethanol consumed and the associated blood ethanol concentrations (BECs). For the HDID lines, this variation occurs even though the residual genetic variation associated with the DID phenotype has been largely exhausted and thus is most likely associated with epigenetic factors. Here we focus on the question of whether the genes associated with individual variation in HDID-1 mice are different from those associated with selection (risk) (Iancu et al., 2013). Thirty-three HDID-1 mice were phenotyped for their BECs at the end of a standard DID trial, were sacrificed 3 weeks later, and RNA-Seq was used to analyze the striatal transcriptome. The data obtained illustrate that there is considerable overlap of the risk and variation gene sets, both focused on the fine-tuning of synaptic plasticity.

Anaplastic lymphoma kinase is a regulator of alcohol consumption and excitatory synaptic plasticity in the nucleus accumbens shell - Mangieri, RA; Maier, EY; Buske, TR; Lasek, AW; Morrisett, RA (Frontiers in Pharmacology, 2017)
Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase recently implicated in biochemical, physiological, and behavioral responses to ethanol. Thus, manipulation of ALK signaling may represent a novel approach to treating alcohol use disorder (AUD). Ethanol induces adaptations in glutamatergic synapses onto nucleus accumbens shell (NAcSh) medium spiny neurons (MSNs), and putative targets for treating AUD may be validated for further development by assessing how their manipulation modulates accumbal glutamatergic synaptic transmission and plasticity. Here, we report that Alk knockout (AlkKO) mice consumed greater doses of ethanol, relative to wild-type (AlkWT) mice, in an operant self-administration model. Using ex vivo electrophysiology to examine excitatory synaptic transmission and plasticity at NAcSh MSNs that express dopamine D1 receptors (D1MSNs), we found that the amplitude of spontaneous excitatory post-synaptic currents (EPSCs) in NAcSh D1MSNs was elevated in AlkKO mice and in the presence of an ALK inhibitor, TAE684. Furthermore, when ALK was absent or inhibited, glutamatergic synaptic plasticity - long-term depression of evoked EPSCs - in D1MSNs was attenuated. Thus, loss of ALK activity in mice is associated with elevated ethanol consumption and enhanced excitatory transmission in NAcSh D1MSNs. These findings add to the mounting evidence of a relationship between excitatory synaptic transmission onto NAcSh D1MSNs and ethanol consumption, point toward ALK as one important molecular mediator of this interaction, and further validate ALK as a target for therapeutic intervention in the treatment of AUD.

Anaplastic lymphoma kinase regulates binge-like drinking and dopamine receptor sensitivity in the ventral tegmental area. - Dutton JW 3rd,; Chen H,; You C,; Brodie MS,; Lasek AW. (Addiction Biology, 2017)
Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase associated with alcohol dependence in humans and behavioral responses to ethanol in mice. To characterize the ability of ALK to control ethanol consumption, we treated mice with the ALK inhibitors TAE684 or alectinib before testing them for binge-like drinking using the drinking in the dark protocol. Mice treated with ALK inhibitors drank less ethanol than controls. In addition, TAE684 treatment abolished ethanol conditioned place preference, indicating that ALK regulates the rewarding properties of ethanol. Because the ventral tegmental area (VTA) is a key brain region involved in the rewarding effects of ethanol, we determined if Alk expression in the VTA is important for binge-like ethanol consumption. Mice expressing a short hairpin ribonucleic acid targeting Alk in the VTA drank less ethanol compared with controls. ALK is expressed on dopamine (DA) neurons in the VTA, suggesting that ALK might regulate their firing properties. Extracellular recordings of putative DA neurons in VTA slices demonstrated that ALK inhibition did not affect the ability of ethanol to stimulate, or DA to inhibit, the firing of DA neurons. However, inhibiting ALK attenuated the time-dependent reversal of inhibition produced by moderate concentrations of DA, suggesting that ALK affects DA D2 autoreceptor (D2R) desensitization. Altered desensitization of the D2R changes the firing of DA neurons and is predicted to affect DA levels and alcohol drinking. These data support the possibility that ALK might be a novel target of pharmacotherapy for reducing excessive alcohol consumption.

Chronic alcohol exposure disrupts CB1 regulation of GABAergic transmission in the rat basolateral amygdala - Varodayan, FP; Bajo, M; Soni, N; Luu, G; Madamba, SG; Schweitzer, P; Roberto, M (Addiction Biology, 2017)
The basolateral nucleus of the amygdala (BLA) is critical to the pathophysiology of anxiety-driven alcohol drinking and relapse. The endogenous cannabinoid/type 1 cannabinoid receptor (eCB/CB1 ) system curbs BLA-driven anxiety and stress responses via a retrograde negative feedback system that inhibits neurotransmitter release, and BLA CB1 activation reduces GABA release and drives anxiogenesis. Additionally, decreased amygdala CB1 is observed in abstinent alcoholic patients and ethanol withdrawn rats. Here, we investigated the potential disruption of eCB/CB1 signaling on GABAergic transmission in BLA pyramidal neurons of rats exposed to 2-3 weeks intermittent ethanol. In the naïve rat BLA, the CB1 agonist WIN 55,212-2 (WIN) decreased GABA release, and this effect was prevented by the CB1 antagonist AM251. AM251 alone increased GABA release via a mechanism requiring postsynaptic calcium-dependent activity. This retrograde tonic eCB/CB1 signaling was diminished in chronic ethanol exposed rats, suggesting a functional impairment of the eCB/CB1 system. In contrast, acute ethanol increased GABAergic transmission similarly in naïve and chronic ethanol exposed rats, via both presynaptic and postsynaptic mechanisms. Notably, CB1 activation impaired ethanol's facilitation of GABAergic transmission across both groups, but the AM251-induced and ethanol-induced facilitation of GABA release was additive, suggesting independent presynaptic sites of action. Collectively, the present findings highlight a critical CB1 influence on BLA GABAergic transmission that is dysregulated by chronic ethanol exposure and, thus, may contribute to the alcohol-dependent state

CNS cell-type localization and LPS response of TLR signaling pathways - McCarthy, GM; Bridges, CR; Blednov, YA; Harris, R A (F1000 Research, 2017)
Background: Innate immune signaling in the brain has emerged as a contributor to many central nervous system (CNS) pathologies, including mood disorders, neurodegenerative disorders, neurodevelopmental disorders, and addiction. Toll-like receptors (TLRs), a key component of the innate immune response, are particularly implicated in neuroimmune dysfunction. However, most of our understanding about TLR signaling comes from the peripheral immune response, and it is becoming clear that the CNS immune response is unique. One controversial aspect of neuroimmune signaling is which CNS cell types are involved. While microglia are the CNS cell-type derived from a myeloid lineage, studies suggest that other glial cell types and even neurons express TLRs, although this idea is controversial. Furthermore, recent work suggests a discrepancy between RNA and protein expression within the CNS. Methods: To elucidate the CNS cell-type localization of TLRs and their downstream signaling molecules, we isolated microglia and astrocytes from the brain of adult mice treated with saline or the TLR4 ligand lipopolysaccharide (LPS). Glial mRNA and protein expression was compared to a cellular-admixture to determine cell-type enrichment. Results: Enrichment analysis revealed that most of the TLR pathway genes are localized in microglia and changed in microglia following immune challenge. However, expression of Tlr3 was enriched in astrocytes, where it increased in response to LPS. Furthermore, attempts to determine protein cell-type localization revealed that many antibodies are non-specific and that antibody differences are contributing to conflicting localization results. Conclusions: Together these results highlight the cell types that should be looked at when studying TLR signaling gene expression and suggest that non-antibody approaches need to be used to accurately evaluate protein expression

Control of chronic excessive alcohol drinking by genetic manipulation of the Edinger-Westphal nucleus urocortin-1 neuropeptide system - Giardino, W. J.; Rodriguez, E. D.; Smith, M. L.; Ford, M. M.; Galili, D.; Mitchell, S. H.; Chen, A.; Ryabinin, A. E. (Translational Psychiatry, 2017)
Midbrain neurons of the centrally projecting Edinger-Westphal nucleus (EWcp) are activated by alcohol, and enriched with stress-responsive neuropeptide modulators (including the paralog of corticotropin-releasing factor, urocortin-1). Evidence suggests that EWcp neurons promote behavioral processes for alcohol-seeking and consumption, but a definitive role for these cells remains elusive. Here we combined targeted viral manipulations and gene array profiling of EWcp neurons with mass behavioral phenotyping in C57BL/6 J mice to directly define the links between EWcp-specific urocortin-1 expression and voluntary binge alcohol intake, demonstrating a specific importance for EWcp urocortin-1 activity in escalation of alcohol intake.

The corticotropin releasing factor receptor 1 in alcohol use disorder: still a valid drug target? - Pomrenze, MB; Fetterly, TL; Winder, DG; Messing, RO (Alcoholism: Clinical and Experimental Research, 2017)
Corticotropin releasing factor (CRF) is a neuropeptide that plays a key role in behavioral and physiological responses to stress. A large body of animal literature implicates CRF acting at type 1 CRF receptors (CRFR1) in consumption by alcohol‐dependent subjects, stress‐induced reinstatement of alcohol seeking, and possibly binge alcohol consumption. These studies have encouraged recent pilot studies of CRFR1 antagonists in humans with alcohol use disorder (AUD). It was a great disappointment to many in the field that these studies failed to show an effect of these compounds on stress‐induced alcohol craving. Here, we examine these studies to explore potential limitations and discuss preclinical and human literature to ask whether CRFR1 is still a valid drug target to pursue for the treatment of AUD.

Corticotropin-releasing factor (CRF) and addictive behaviors - Roberto, M; Spierling, SR; Kirson, D; Zorrilla, EP (International Review of Neurobiology, 2017)
Drug addiction is a complex disorder that is characterized by compulsivity to seek and take the drug, loss of control in limiting intake of the drug, and emergence of a withdrawal syndrome in the absence of the drug. The transition from casual drug use to dependence is mediated by changes in reward and brain stress functions and has been linked to a shift from positive reinforcement to negative reinforcement. The recruitment of brain stress systems mediates the negative emotional state produced by dependence that drives drug seeking through negative reinforcement mechanisms, defined as the "dark side" of addiction. In this chapter we focus on behavioral and cellular neuropharmacological studies that have implicated brain stress systems (i.e., corticotropin-releasing factor [CRF]) in the transition to addiction and the predominant brain regions involved. We also discuss the implication of CRF recruitment in compulsive eating disorders.

CRF modulates glutamate transmission in the central amygdala of naïve and ethanol-dependent rats - Varodayan, FP; Correia, D; Kirson, D; Khom, S; Oleata, CS; Luu, G; Schweitzer, P; Roberto, M (Neuropharmacology, 2017)
Corticotropin-releasing factor (CRF) signaling in the central nucleus of the amygdala (CeA) is hypothesized to drive the development of alcohol dependence, as it regulates ethanol intake and several anxiogenic behaviors linked to withdrawal. Excitatory glutamatergic neurotransmission contributes to alcohol reinforcement, tolerance and dependence. Therefore, in this study we used in vitro slice electrophysiology to investigate the effects of CRF and its receptor subtype (CRF1 and CRF2) antagonists on both evoked and spontaneous action potential-independent glutamatergic transmission in the CeA of naive and ethanol-dependent Sprague-Dawley rats. We found that CRF (25-200 nM) concentration-dependently diminished evoked compound excitatory postsynaptic potentials (EPSPs), but increased miniature excitatory postsynaptic current (mEPSC) frequencies similarly in CeA neurons of both naïve and ethanol-dependent rats, indicating reduced evoked glutamatergic responses and enhanced vesicular glutamate release, respectively. This CRF-induced vesicular glutamate release was prevented by the CRF1/2 antagonist (Astressin B) and the CRF1 antagonist (R121919), but not by the CRF2 antagonist (Astressin 2B). Similarly, CRF's effects on evoked glutamatergic responses were completely blocked by CRF1 antagonism, but only slightly decreased in the presence of the CRF2 antagonist. Moreover, CRF1 antagonism reveals a tonic facilitation of vesicular glutamate, whereas the CRF2 antagonism revealed a tonic inhibition of vesicular glutamate release. Collectively our data show that CRF primarily acts at presynaptic CRF1 to produce opposite effects on CeA evoked and spontaneous glutamate release and that the CRF system modulates CeA glutamatergic synapses throughout the development of alcohol dependence.

DNA modifications in models of alcohol use disorders - Tulisiak, CT; Harris, R A; Ponomarev, I (Alcohol, 2017)
Chronic alcohol use and abuse result in widespread changes to gene expression, some of which contribute to the development of alcohol-use disorders (AUD). Gene expression is controlled, in part, by a group of regulatory systems often referred to as epigenetic factors, which includes, among other mechanisms, chemical marks made on the histone proteins around which genomic DNA is wound to form chromatin, and on nucleotides of the DNA itself. In particular, alcohol has been shown to perturb the epigenetic machinery, leading to changes in gene expression and cellular functions characteristic of AUD and, ultimately, to altered behavior. DNA modifications in particular are seeing increasing research in the context of alcohol use and abuse. To date, studies of DNA modifications in AUD have primarily looked at global methylation profiles in human brain and blood, gene-specific methylation profiles in animal models, methylation changes associated with prenatal ethanol exposure, and the potential therapeutic abilities of DNA methyltransferase inhibitors. Future studies may be aimed at identifying changes to more recently discovered DNA modifications, utilizing new methods to discriminate methylation profiles between cell types, thus clarifying how alcohol influences the methylomes of cell-type populations and how this may affect downstream processes. These studies and more in-depth probing of DNA methylation will be key to determining whether DNA-level epigenetic regulation plays a causative role in AUD and can thus be targeted for treatment of the disorder.

DNA modifications in models of alcohol use disorders - Tulisiak, CT; Harris, R A; Ponomarev, I (Alcohol, 2017)
Chronic alcohol use and abuse result in widespread changes to gene expression, some of which contribute to the development of alcohol-use disorders (AUD). Gene expression is controlled, in part, by a group of regulatory systems often referred to as epigenetic factors, which includes, among other mechanisms, chemical marks made on the histone proteins around which genomic DNA is wound to form chromatin, and on nucleotides of the DNA itself. In particular, alcohol has been shown to perturb the epigenetic machinery, leading to changes in gene expression and cellular functions characteristic of AUD and, ultimately, to altered behavior. DNA modifications in particular are seeing increasing research in the context of alcohol use and abuse. To date, studies of DNA modifications in AUD have primarily looked at global methylation profiles in human brain and blood, gene-specific methylation profiles in animal models, methylation changes associated with prenatal ethanol exposure, and the potential therapeutic abilities of DNA methyltransferase inhibitors. Future studies may be aimed at identifying changes to more recently discovered DNA modifications, utilizing new methods to discriminate methylation profiles between cell types, thus clarifying how alcohol influences the methylomes of cell-type populations and how this may affect downstream processes. These studies and more in-depth probing of DNA methylation will be key to determining whether DNA-level epigenetic regulation plays a causative role in AUD and can thus be targeted for treatment of the disorder.

Effects of selection for ethanol preference on gene expression in the nucleus accumbens of HS-CC mice. - Colville AM,; Iancu OD,; Oberbeck DL,; Darakjian P,; Zheng CL,; Walter NA,; Harrington CA,; Searles RP,; McWeeney S,; Hitzemann RJ. (Genes Brain and Behavior, 2017)
Previous studies on changes in murine brain gene expression associated with the selection for ethanol preference have used F2 intercross or heterogeneous stock (HS) founders, derived from standard laboratory strains. However, these populations represent only a small proportion of the genetic variance available in Mus musculus. To investigate a wider range of genetic diversity, we selected mice for ethanol preferenceusing an HS derived from the eight strains of the collaborative cross. These HS mice were selectively bred (four generations) for high and low ethanol preference. The nucleus accumbens shell of naive S4 mice was interrogated using RNA sequencing (RNA-Seq). Gene networks were constructed using the weighted gene coexpression network analysis assessing both coexpression and cosplicing. Selection targeted one of the network coexpression modules (greenyellow) that was significantly enriched in genes associated with receptor signaling activity including Chrna7, Grin2a, Htr2a and Oprd1. Connectivity in the module as measured by changes in the hub nodes was significantly reduced in the low preference line. Of particular interest was the observation that selection had marked effects on a large number of cell adhesion molecules, including cadherins and protocadherins. In addition, the coexpression data showed that selection had marked effects on long non-coding RNA hub nodes. Analysis of the cosplicing network data showed a significant effect of selection on a large cluster of Ras GTPase-binding genes including Cdkl5, Cyfip1, Ndrg1, Sod1 and Stxbp5. These data in part support the earlier observation that preference is linked to Ras/Mapk pathways.

Emerging roles for ncRNAs in alcohol use disorders - Mayfield, R D (Alcohol, 2017)
Chronic alcohol exposure produces widespread neuroadaptations and alterations in gene expression in human alcoholics and animal models. Technological advances in the past decade have increasingly highlighted the role of non-protein-coding RNAs (ncRNAs) in the regulation of gene expression and function. These recently characterized molecules were discovered to mediate diverse processes in the central nervous system, from normal development and physiology to regulation of disease, including alcoholism and other psychiatric disorders. This review will investigate the recent studies in human alcoholics and rodent models that have profiled different classes of ncRNAs and their dynamic alcohol-dependent regulation in brain.

Epigenetic mediators and consequences of excessive alcohol consumption. - Mahnke AH,; Miranda RC,; Homanics GE. (Alcohol, 2017)
Alcohol has pleiotropic effects across multiple organ systems, including brain, cardio-vascular, endocrine, immune, musculoskeletal, and gastrointestinal systems. Moreover, some effects, such as intoxication, can be brief, but others, such as the development of Alcohol Use Disorders (AUDs), cardiovascular disease, and liver damage, can persist for a lifetime. Effects resulting in encoding of endocrine and other dysfunctions can also persist across generations. This complexity creates a barrier to the creation of therapeutics and discovery of biomarkers. However, we know that environmental factors, which can include drugs of abuse such as alcohol, can have short- and long-term effects on gene expression through epigenetic mechanisms (Holliday, 2006, Shukla et al., 2008). Epigenetic mechanisms affect the transcription and translation of many genes simultaneously. Therefore, by understanding the mechanics of these epigenetic changes, we will have the ability to craft powerful new therapeutics to offset negative effects of alcohol exposure.

Estradiol increases the sensitivity of ventral tegmental area dopamine neurons to dopamine and ethanol - Vandegrift, BJ; You, C; Satta, R; Brodie, MS; Lasek, AW (PLoS One, 2017)
Gender differences in psychiatric disorders such as addiction may be modulated by the steroid hormone estrogen. For instance, 17β-estradiol (E2), the predominant form of circulating estrogen in pre-menopausal females, increases ethanol consumption, suggesting that E2 may affect the rewarding properties of ethanol and thus the development of alcohol use disorder in females. The ventral tegmental area (VTA) is critically involved in the rewarding and reinforcing effects of ethanol. In order to determine the role of E2 in VTA physiology, gonadally intact female mice were sacrificed during diestrus II (high E2) or estrus (low E2) for electrophysiology recordings. We measured the excitation by ethanol and inhibition by dopamine (DA) of VTA DA neurons and found that both excitation by ethanol and inhibition by dopamine were greater in diestrus II compared with estrus. Treatment of VTA slices from mice in diestrus II with an estrogen receptor antagonist (ICI 182,780) reduced ethanol-stimulated neuronal firing, but had no effect on ethanol-stimulated firing of neurons in slices from mice in estrus. Surprisingly, ICI 182,780 did not affect the inhibition by DA, indicating different mechanisms of action of estrogen receptors in altering ethanol and DA responses. We also examined the responses of VTA DA neurons to ethanol and DA in ovariectomized mice treated with E2 and found that E2 treatment enhanced the responses to ethanol and DA in a manner similar to what we observed in mice in diestrus II. Our data indicate that E2 modulates VTA neuron physiology, which may contribute to both the enhanced reinforcing and rewarding effects of alcohol and the development of other psychiatric disorders in females that involve alterations in DA neurotransmission.

Executive functions, memory, and social cognitive deficits and recovery in chronic alcoholism: a critical review to inform future research. - Le Berre AP,; Fama R,; Sullivan EV (Alcoholism: Clinical and Experimental Research, 2017)
Alcoholism is a complex and dynamic disease, punctuated by periods of abstinence and relapse, and influenced by a multitude of vulnerability factors. Chronic excessive alcohol consumption is associated with cognitive deficits, ranging from mild to severe, in executivefunctions, memory, and metacognitive abilities, with associated impairment in emotional processes and social cognition. These deficits can compromise efforts in initiating and sustaining abstinence by hampering efficacy of clinical treatment and can obstruct efforts in enabling good decision making success in interpersonal/social interactions, and awareness of cognitive and behavioral dysfunctions. Despite evidence for differences in recovery levels of selective cognitive processes, certain deficits can persist even with prolonged sobriety. Herein is presented a review of alcohol-related cognitive impairments affecting component processes of executive functioning, memory, and the recently investigated cognitive domains of metamemory, social cognition, and emotional processing; also considered are trajectories of cognitiverecovery with abstinence. Finally, in the spirit of critical review, limitations of current knowledge are noted and avenues for new researchefforts are proposed that focus on (i) the interaction among emotion-cognition processes and identification of vulnerability factors contributing to the development of emotional and social processing deficits and (ii) the time line of cognitive recovery by tracking alcoholism's dynamic course of sobriety and relapse. Knowledge about the heterochronicity of cognitive recovery in alcoholism has the potential of indicating at which points during recovery intervention may be most beneficial.

Gabapentin for the treatment of alcohol use disorder - Mason, BJ; Quello, S; Shadan, F (Expert Opinion on Investigational Drugs, 2017)
Alcohol misuse is the fifth leading risk factor for premature death and disability worldwide. Fewer than 10% of afflicted Americans receive pharmacological treatment for alcohol use disorder. Gabapentin is a calcium channel GABAergic modulator that is widely used for pain. Studies showing reduced drinking and decreased craving and alcohol-related disturbances in sleep and affect in the months following alcohol cessation suggest therapeutic potential for alcohol use disorder. Areas covered: Human laboratory and clinical studies assessing gabapentin for alcohol use disorder are reviewed. Data were obtained by searching for English peer-reviewed articles on PubMed, reference lists of identified articles, and trials registered on clinicaltrials.gov. Additionally, the mechanism of action of gabapentin specific to alcohol use disorder, and studies of gabapentin for alcohol withdrawal and non-alcohol substance use disorders are summarized. Expert opinion: Alcohol use disorder represents a challenge and large, unmet medical need. Evidence from single-site studies lend support to the safety and efficacy of gabapentin as a novel treatment for alcohol use disorder, with unique benefits for alcohol-related insomnia and negative affect, relative to available treatments. Proprietary gabapentin delivery systems may open a path to pivotal trials and registration of gabapentin as a novel treatment for alcohol use disorder.

Gender differences in risk factors for adolescent binge drinking and implications for intervention and prevention. - Dir AL,; Bell RL,; Adams ZW,; Hulvershorn LA. (Frontiers in Psychiatry, 2017)
Alcohol use, particularly binge drinking (BD), is a major public health concern among adolescents. Recent national data show that the gendergap in alcohol use is lessening, and BD among girls is rising. Considering the increase in BD among adolescent girls, as well as females' increased risk of experiencing more severe biopsychosocial negative effects and consequences from BD, the current review sought to examine gender differences in risk factors for BD. The review highlights gender differences in (1) developmental-related neurobiological vulnerability to BD, (2) psychiatric comorbidity and risk phenotypes for BD, and (3) social-related risk factors for BD among adolescents, as well as considerations for BD prevention and intervention. Most of the information gleaned thus far has come from preclinical research. However, it is expected that, with recent advances in clinical imaging technology, neurobiological effects observed in lower mammals will be confirmed in humans and vice versa. A synthesis of the literature highlights that males and females experience unique neurobiological paths of development, and although there is debate regarding the specific nature of these differences, literature suggests that these differences in turn influence gender differences in psychiatric comorbidity and risk for BD. For one, girls are more susceptible to stress, depression, and other internalizing behaviors and, in turn, these symptoms contribute to their risk for BD. On the other hand, males, given gender differencesacross the lifespan as well as gender differences in development, are driven by an externalizing phenotype for risk of BD, in part, due to unique paths of neurobiological development that occur across adolescence. With respect to social domains, although social and peer influences are important for both adolescent males and females, there are gender differences. For example, girls may be more sensitive to pressure from peers to fit in and impress others, while male gender role stereotypes regarding BD may be more of a risk factor for boys. Given these unique differences in male and female risk for BD, further research exploring risk factors, as well as tailoring intervention and prevention, is necessary. Although recent research has tailored substance use intervention to target males and females, more literature on gender considerations in treatment for prevention and intervention of BD in particular is warranted.

Gene expression changes in the ventral hippocampus and medial prefrontal cortex of adolescent alcohol-preferring (P) rats following binge-like alcohol drinking - McClintick, JN; McBride, WJ; Bell, RL; Ding, ZM; Liu, Y; Xuei, X; Edenberg, HJ (Alcohol, 2017)
Binge drinking of alcohol during adolescence is a serious public health concern with long-term consequences, including decreased hippocampal and prefrontal cortex volume and deficits in memory. We used RNA sequencing to assess the effects of adolescent binge drinking on gene expression in these regions. Male adolescent alcohol-preferring (P) rats were exposed to repeated binge drinking (three 1-h sessions/day during the dark/cycle, 5 days/week for 3 weeks starting at 28 days of age; ethanol intakes of 2.5-3 g/kg/session). Ethanol significantly altered the expression of 416 of 11,727 genes expressed in the ventral hippocampus. Genes and pathways involved in neurogenesis, long-term potentiation, and axonal guidance were decreased, which could relate to the impaired memory function found in subjects with adolescent alcohol binge-like exposure. The decreased expression of myelin and cholesterol genes and apparent decrease in oligodendrocytes in P rats could result in decreased myelination. In the medial prefrontal cortex, 638 of 11,579 genes were altered; genes in cellular stress and inflammatory pathways were increased, as were genes involved in oxidative phosphorylation. Overall, the results of this study suggest that adolescent binge-like alcohol drinking may alter the development of the ventral hippocampus and medial prefrontal cortex and produce long-term consequences on learning and memory, and on control of impulsive behaviors.

Gene expression profiling in the human alcoholic brain - Warden, AS; Mayfield, R D (Neuropharmacology, 2017)
Long-term alcohol use causes widespread changes in gene expression in the human brain. Aberrant gene expression changes likely contribute to the progression from occasional alcohol use to alcohol use disorder (including alcohol dependence). Transcriptome studies have identified individual gene candidates that are linked to alcohol-dependence phenotypes. The use of bioinformatics techniques to examine expression datasets has provided novel systems-level approaches to transcriptome profiling in human postmortem brain. These analytical advances, along with recent developments in next-generation sequencing technology, have been instrumental in detecting both known and novel coding and non-coding RNAs, alternative splicing events, and cell-type specific changes that may contribute to alcohol-related pathologies. This review offers an integrated perspective on alcohol-responsive transcriptional changes in the human brain underlying the regulatory gene networks that contribute to alcohol dependence. This article is part of the Special Issue entitled "Alcoholism".

Genetic and Pharmacologic Manipulation of TLR4 Has Minimal Impact on Ethanol Consumption in Rodents - Harris, R. Adron; Bajo, Michal; Bell, Richard L.; Blednov, Yuri A.; Varodayan, Florence P.; Truitt, Jay M.; de Guglielmo, Giordano; Lasek, Amy W.; Logrip, Marian L.; Vendruscolo, Leandro F.; Roberts, Amanda J.; Roberts, Edward; et al. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2017)
Toll-like receptor 4 (TLR4) is a critical component of innate immune signaling and has been implicated in alcohol responses in preclinical and clinical models. Members of the Integrative Neuroscience Initiative on Alcoholism (INIA-Neuroimmune) consortium tested the hypothesis that TLR4 mediates excessive ethanol drinking using the following models: (1) Tlr4 knock-out (KO) rats, (2) selective knockdown of Tlr4 mRNA in mouse nucleus accumbens (NAc), and (3) injection of the TLR4 antagonist (+)-naloxone in mice. Lipopolysaccharide (LPS) decreased food/water intake and body weight in ethanol-naive and ethanol-trained wild-type (WT), but not Tlr4 KO rats. There were no consistent genotypic differences in two-bottle choice chronic ethanol intake or operant self-administration in rats before or after dependence. In mice, (+)-naloxone did not decrease drinking-in-the-dark and only modestly inhibited dependence-driven consumption at the highest dose. Tlr4 knockdown in mouse NAc did not decrease drinking in the two-bottle choice continuous or intermittent access tests. However, the latency to ethanol-induced loss of righting reflex increased and the duration decreased in KO versus WT rats. In rat central amygdala neurons, deletion of Tlr4 altered GABAA receptor function, but not GABA release. Although there were no genotype differences in acute ethanol effects before or after chronic intermittent ethanol exposure, genotype differences were observed after LPS exposure. Using different species and sexes, different methods to inhibit TLR4 signaling, and different ethanol consumption tests, our comprehensive studies indicate that TLR4 may play a role in ethanol-induced sedation and GABAA receptor function, but does not regulate excessive drinking directly and would not be an effective therapeutic target. SIGNIFICANCE STATEMENT: Toll-like receptor 4 (TLR4) is a key mediator of innate immune signaling and has been implicated in alcohol responses in animal models and human alcoholics. Members of the Integrative Neuroscience Initiative on Alcoholism (INIA-Neuroimmune) consortium participated in the first comprehensive study across multiple laboratories to test the hypothesis that TLR4 regulates excessive alcohol consumption in different species and different models of chronic, dependence-driven, and binge-like drinking. Although TLR4 was not a critical determinant of excessive drinking, it was important in the acute sedative effects of alcohol. Current research efforts are directed at determining which neuroimmune pathways mediate excessive alcohol drinking and these findings will help to prioritize relevant pathways and potential therapeutic targets.
Keywords: (+)-naloxone; chronic intermittent ethanol vapor; Drinking-in-the-dark; Lipopolysaccharide; Operant self-administration; Toll-like receptor 4 knock-out

Glycine receptor α3 and α2 subunits mediate tonic and exogenous agonist-induced currents in forebrain - McCracken, LM; Lowes, DC; Salling, MC; Carreau-Vollmer, C; Odean, NN; Blednov, YA; Betz, H; Harris, R A; Harrison, NL (Proceedings of the National Academy of Sciences USA, 2017)
Neuronal inhibition can occur via synaptic mechanisms or through tonic activation of extrasynaptic receptors. In spinal cord, glycine mediates synaptic inhibition through the activation of heteromeric glycine receptors (GlyRs) composed primarily of α1 and β subunits. Inhibitory GlyRs are also found throughout the brain, where GlyR α2 and α3 subunit expression exceeds that of α1, particularly in forebrain structures, and coassembly of these α subunits with the β subunit appears to occur to a lesser extent than in spinal cord. Here, we analyzed GlyR currents in several regions of the adolescent mouse forebrain (striatum, prefrontal cortex, hippocampus, amygdala, and bed nucleus of the stria terminalis). Our results show ubiquitous expression of GlyRs that mediate large-amplitude currents in response to exogenously applied glycine in these forebrain structures. Additionally, tonic inward currents were also detected, but only in the striatum, hippocampus, and prefrontal cortex (PFC). These tonic currents were sensitive to both strychnine and picrotoxin, indicating that they are mediated by extrasynaptic homomeric GlyRs. Recordings from mice deficient in the GlyR α3 subunit (Glra3-/-) revealed a lack of tonic GlyR currents in the striatum and the PFC. In Glra2-/Y animals, GlyR tonic currents were preserved; however, the amplitudes of current responses to exogenous glycine were significantly reduced. We conclude that functional α2 and α3 GlyRs are present in various regions of the forebrain and that α3 GlyRs specifically participate in tonic inhibition in the striatum and PFC. Our findings suggest roles for glycine in regulating neuronal excitability in the forebrain.

High Drinking in the Dark (HDID) mice are sensitive to the effects of some clinically relevant drugs to reduce binge-like drinking. - Crabbe JC, (Pharmacology Biochemistry and Behavior, 2017)
There is a serious public health need for better understanding of alcohol use disorder disease mechanisms and for improved treatments. At this writing, only three drugs are approved by the Food and Drug Administration as medications to treat alcohol use disorders - disulfiram, naltrexone, and acamprosate. Binge drinking is a form of abusive alcohol drinking defined by the NIAAA as a drinkingto blood alcohol levels (BALs)>0.08% during a period of approximately 2h. To model genetic risk for binge-like drinking, we have used selective breeding to create a unique animal model, High Drinking in the Dark (HDID) mice. Behavioral characterization of HDID mice has revealed that HDID mice exhibit behavioral impairment after drinking, withdrawal after a single binge-drinking session, and escalate their intake in response to induction of successive cycles of dependence. Notably, HDID mice do not exhibit altered tastant preference or alcohol clearance rates. We therefore asked whether drugs of known clinical relevance could modulate binge-like ethanol drinking in HDID mice, reasoning that this characterization of HDID responses should inform future use of this genetic animal model for screening and development of novel potential therapeutics.

Inhibition of IKKβ reduces ethanol consumption in C57BL/6J mice - Truitt, JM; Blednov, YA; Benavidez, JM; Black, M; Ponomareva, O; Law, J; Merriman, M; Horani, S; Jameson, K; Lasek, AW; Harris, R A; Mayfield, R D (eNeuro, 2017)
Proinflammatory pathways in neuronal and non-neuronal cells are implicated in the acute and chronic effects of alcohol exposure in animal models and humans. The nuclear factor-κB (NF-κB) family of DNA transcription factors plays important roles in inflammatory diseases. The kinase IKKβ mediates the phosphorylation and subsequent proteasomal degradation of cytosolic protein inhibitors of NF-κB, leading to activation of NF-κB. The role of IKKβ as a potential regulator of excessive alcohol drinking had not previously been investigated. Based on previous findings that the overactivation of innate immune/inflammatory signaling promotes ethanol consumption, we hypothesized that inhibiting IKKβ would limit/decrease drinking by preventing the activation of NF-κB. We studied the systemic effects of two pharmacological inhibitors of IKKβ, TPCA-1 and sulfasalazine, on ethanol intake using continuous- and limited-access, two-bottle choice drinking tests in C57BL/6J mice. In both tests, TPCA-1 and sulfasalazine reduced ethanol intake and preference without changing total fluid intake or sweet taste preference. A virus expressing Cre recombinase was injected into the nucleus accumbens and central amygdala to selectively knock down IKKβ in mice genetically engineered with a conditional Ikkb deletion (IkkbF/F ). Although IKKβ was inhibited to some extent in astrocytes and microglia, neurons were a primary cellular target. Deletion of IKKβ in either brain region reduced ethanol intake and preference in the continuous access two-bottle choice test without altering the preference for sucrose. Pharmacological and genetic inhibition of IKKβ decreased voluntary ethanol consumption, providing initial support for IKKβ as a potential therapeutic target for alcohol abuse.

Mechanistic insights into epigenetic modulation of ethanol consumption - Ponomarev, I; Stelly, CE; Morikawa, H; Blednov, YA; Mayfield, R D; Harris, R A (Alcohol, 2017)
There is growing evidence that small-molecule inhibitors of epigenetic modulators, such as histone deacetylases (HDAC) and DNA methyltransferases (DNMT), can reduce voluntary ethanol consumption in animal models, but molecular and cellular processes underlying this behavioral effect are poorly understood. We used C57BL/6J male mice to investigate the effects of two FDA-approved drugs, decitabine (a DNMT inhibitor) and SAHA (an HDAC inhibitor), on ethanol consumption using two tests: binge-like drinking in the dark (DID) and chronic intermittent every other day (EOD) drinking. Decitabine but not SAHA reduced ethanol consumption in both tests. We further investigated decitabine's effects on the brain's reward pathway by gene expression profiling in the ventral tegmental area (VTA), using RNA sequencing and electrophysiological recordings from VTA dopaminergic neurons. Decitabine-induced decreases in EOD drinking were associated with global changes in gene expression, implicating regulation of cerebral blood flow, extracellular matrix organization, and neuroimmune functions in decitabine actions. In addition, an in vivo administration of decitabine shortened ethanol-induced excitation of VTA dopaminergic neurons in vitro, suggesting that decitabine reduces ethanol drinking via changes in the reward pathway. Taken together, our data suggest a contribution of both neuronal and non-neuronal mechanisms in the VTA in the regulation of ethanol consumption. Decitabine and other epigenetic compounds have been approved for cancer treatment, and understanding their mechanisms of actions in the brain may assist in repurposing these drugs and developing novel therapies for central disorders, including drug addiction.

Microglial-specific transcriptome changes following chronic alcohol consumption - McCarthy, GM; Farris, SP; Blednov, YA; Harris, R A; Mayfield, R D (Neuropharmacology, 2017)
Microglia are fundamentally important immune cells within the central nervous system (CNS) that respond to environmental challenges to maintain normal physiological processes. Alterations in steady-state cellular function and over-activation of microglia can facilitate the initiation and progression of neuropathological conditions such as Alzheimer's disease, Multiple Sclerosis, and Major Depressive Disorder. Alcohol consumption disrupts signaling pathways including both innate and adaptive immune responses that are necessary for CNS homeostasis. Coordinate expression of these genes is not ascertained from an admixture of CNS cell-types, underscoring the importance of examining isolated cellular populations to reveal systematic gene expression changes arising from mature microglia. Unbiased RNA-Seq profiling was used to identify gene expression changes in isolated prefrontal cortical microglia in response to recurring bouts of voluntary alcohol drinking behavior. The voluntary ethanol paradigm utilizes long-term consumption ethanol that results in escalated alcohol intake and altered cortical plasticity that is seen in humans. Gene coexpression analysis identified a coordinately regulated group of genes, unique to microglia, that collectively are associated with alcohol consumption. Genes within this group are involved in toll-like receptor signaling and transforming growth factor beta signaling. Network connectivity of this group identified Siglech as a putative hub gene and highlighted the potential importance of proteases in the microglial response to chronic ethanol. In conclusion, we identified a distinctive microglial gene expression signature for neuroimmune responses related to alcohol consumption that provides valuable insight into microglia-specific changes underlying the development of substance abuse, and possibly other CNS disorders.

Midkine in the mouse ventral tegmental area limits ethanol intake and Ccl2 gene expression. - Chen H,; He D,; Lasek AW. (Genes Brain and Behavior, 2017)
Midkine (MDK) is a cytokine and neurotrophic factor that is more highly expressed in the brains of alcoholics and in mice predisposed to drink large amounts of ethanol, suggesting that MDK may regulate ethanol consumption. Here we measured ethanol consumption in male and female Mdk knockout (-/-) mice using the two-bottle choice and the drinking in the dark (DID) tests. We found that Mdk -/- mice consumed significantly more ethanol than wild-type controls in both tests. To determine if MDK acts in the ventral tegmental area (VTA) to regulate ethanol consumption, we delivered lentivirus expressing a Mdk shRNA into the VTA of male C57BL/6J mice to locally knockdown Mdk and performed the DID test. Mice expressing a Mdk shRNA in the VTA consumed more ethanol than mice expressing a control non-targeting shRNA, demonstrating that the VTA is one site in the brain through which MDK acts to regulate ethanol consumption. Since MDK also controls the expression of inflammatory cytokines in other organs, we examined gene expression of interleukin-1 beta (Il1b), tumor necrosis factor alpha (Tnfα) and the chemokine (C-C motif) ligand 2 (Ccl2) in the VTA of Mdk -/- mice and in mice expressing Mdk shRNA in the VTA. Expression of Ccl2 was elevated in the VTA of Mdk -/- mice and in mice expressing Mdk shRNA in the VTA. These results demonstrate that MDK functions in the VTA to limit ethanol consumption and levels of CCL2, a chemokine known to increase ethanol consumption.

Mutation of the inhibitory ethanol site in GABA(A) ρ1 receptors promotes tolerance to ethanol-induced motor incoordination. - Blednov YA,; Borghese CM,; Ruiz CI,; Cullins MA,; Da Costa A,; Osterndorff-Kahanek EA,; Homanics GE,; Harris RA. (Neuropharmacology, 2017)
Genes encoding the ρ1/2 subunits of GABAA receptors have been associated with alcohol (ethanol) dependence in humans, and ρ1 was also shown to regulate some of the behavioral effects of ethanol in animal models. Ethanol inhibits GABA-mediated responses in wild-type (WT) ρ1, but not ρ1(T6'Y) mutant receptors expressed in Xenopus laevis oocytes, indicating the presence of an inhibitory site for ethanol in the second transmembrane helix. In this study, we found that ρ1(T6'Y) receptors expressed in oocytes display overall normal responses to GABA, the endogenous GABA modulator (zinc), and partial agonists (β-alanine and taurine). We generated ρ1 (T6'Y) knockin (KI) mice using CRISPR/Cas9 to test the behavioral importance of the inhibitory actions of ethanol on this receptor. Both ρ1 KI and knockout (KO) mice showed faster recovery from acute ethanol-induced motor incoordination compared to WT mice. Both KI and KO mutant strains also showed increased tolerance to motor impairment produced by ethanol. The KI mice did not differ from WT mice in other behavioral actions, including ethanol intake and preference, conditioned taste aversion to ethanol, and duration of ethanol-induced loss of righting reflex. WT and KI mice did not differ in levels of ρ1 or ρ2 mRNA in cerebellum or in ethanol clearance. Our findings indicate that the inhibitory site for ethanol in GABAA ρ1 receptors regulates acute functional tolerance to moderate ethanol intoxication. We note that low sensitivity to alcohol intoxication has been linked to risk for development of alcohol dependence in humans.

Negative affect-associated USV acoustic characteristics predict future excessive alcohol drinking and alcohol avoidance in male P and NP rats - Reno, JM; Thakore, N; Cormack, LK; Schallert, T; Bell, RL; Maddox, WT; Duvauchelle, CL (Alcoholism: Clinical and Experimental Research, 2017)
BACKGROUND: Negative emotional status and adverse emotional events increase vulnerability to alcohol abuse. Ultrasonic vocalizations (USVs) emitted by rats are a well-established model of emotional status that can reflect positive or negative affective responses in real time. Most USV studies assess counts, yet each USV is a multidimensional data point characterized by several acoustic characteristics that may provide insight into the neurocircuitry underlying emotional response. METHODS: USVs emitted from selectively bred alcohol-naïve and alcohol-experienced alcohol-preferring and nonpreferring rats (P and NP rats) were recorded during 4-hour sessions on alternating days over 4 weeks. Linear mixed modeling (LMM) and linear discriminant analysis (LDA) were applied to USV acoustic characteristics (e.g., frequency, duration, power, and bandwidth) of negative affect (22 to 28 kilohertz [kHz])- and positive (50 to 55 kHz) affect-related USVs. RESULTS: Hundred percent separation between alcohol-naïve P and NP rats was achieved through a linear combination (produced by LDA) of USV acoustic characteristics of 22- to 28-kHz USVs, whereas poor separation (36.5%) was observed for 50- to 55-kHz USVs. 22- to 28-kHz LDA separation was high (87%) between alcohol-experienced P and NP rats, but was poor for 50- to 55-kHz USVs (57.3%). USV mean frequency and duration were the highest weighted characteristics in both the naïve and experienced 22- to 28-kHz LDA representations suggesting that alcohol experience does not alter the representations. LMM analyses of 22- to 28-kHz USV acoustic characteristics matched the LDA results. Poor LDA separation was observed between alcohol-naïve and alcohol-experienced P rats for both 22- to 28-kHz and 50- to 55-kHz USVs. CONCLUSIONS: Advanced statistical analysis of negative affect-associated USV data predicts future behaviors of excessive alcohol drinking and alcohol avoidance in selectively bred rats. USV characteristics across rat lines reveal affect-related motivation to consume alcohol and may predict neural pathways mediating emotional response. Further characterization of these differences could delineate particular neurocircuitry and methods to ameliorate dysregulated emotional states often observed in human alcohol abusers.

The Neuroimmune Basis of Excessive Alcohol Consumption - Mayfield, Jody; Harris, R. Adron (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2017)

Novel molecule exhibiting selective affinity for GABAA receptor subtypes. - Borghese CM,; Herman M,; Snell LD,; Lawrence KJ,; Lee HY,; Backos DS,; Vanderlinden LA,; Harris RA; Roberto M; Hoffman PL,; Tabakoff B. (Scientific Reports, 2017)
Aminoquinoline derivatives were evaluated against a panel of receptors/channels/transporters in radioligand binding experiments. One of these derivatives (DCUK-OEt) displayed micromolar affinity for brain γ-aminobutyric acid type A (GABAA) receptors. DCUK-OEt was shown to be a positive allosteric modulator (PAM) of GABA currents with α1β2γ2, α1β3γ2, α5β3γ2 and α1β3δ GABAA receptors, while having no significant PAM effect on αβ receptors or α1β1γ2, α1β2γ1, α4β3γ2 or α4β3δ receptors. DCUK-OEt modulation of α1β2γ2 GABAA receptors was not blocked by flumazenil. The subunit requirements for DCUK-OEt actions distinguished DCUK-OEt from other currently known modulators of GABA function (e.g., anesthetics, neurosteroids or ethanol). Simulated docking of DCUK-OEt at the GABAA receptorsuggested that its binding site may be at the α + β- subunit interface. In slices of the central amygdala, DCUK-OEt acted primarily on extrasynaptic GABAA receptors containing the α1 subunit and generated increases in extrasynaptic "tonic" current with no significant effect on phasic responses to GABA. DCUK-OEt is a novel chemical structure acting as a PAM at particular GABAA receptors. Given that neurons in the central amygdala responding to DCUK-OEt were recently identified as relevant for alcohol dependence, DCUK-OEt should be further evaluated for the treatment of alcoholism.

The peroxisome proliferator-activated receptor alpha agonist fenofibrate attenuates alcohol self-administration in rats - Haile, Colin N.; Kosten, Therese A. (Neuropharmacology, 2017)
Fibrates are a class of medications used to treat hypercholesterolemia and dyslipidemia that target nuclear peroxisome proliferator-activated receptors (PPARs). Studies have shown the PPARα agonist fenofibrate decreases voluntary EtOH consumption however its impact on the reinforcing and motivational effects of EtOH is unknown. We evaluated the ability of fenofibrate (25, 50 and 100 mg/kg), to alter EtOH (10%, w/v) and sucrose (2%, w/v) operant self-administration in rats under a FR2 schedule of reinforcement over four days and under a progressive ratio (PR) schedule on day five of treatment. Results showed fenofibrate dose-dependently decreased EtOH self-administration under both schedules of reinforcement with the greatest effects seen after four to five days of treatment. Fenofibrate decreased responding for sucrose only under the PR schedule of reinforcement and this effect was not dose-dependent. These findings provide further evidence for fenofibrate as a potential treatment for alcohol use disorder in humans.
Keywords: addiction; alcohol; Drug seeking; Ethanol; Ethanol reinforcement; Peroxisome Proliferator-Activated Receptors; PPARα; Progressive ratio; Rats; self-administration

Perspectives on fronto-fugal circuitry from human imaging of alcohol use disorders - Zahr, NM; Pfefferbaum, A; Sullivan EV (Neuropharmacology, 2017)
Descriptions of the cognitive functions affected by alcohol use disorders (AUD) often highlight dysfunction of executive processes such attention, inhibitory control, working memory, and cognitive flexibility. Such complex cognitive functions have historically been ascribed to the prefrontal cortex. AUD, however, disrupts extensive areas of the brain. Structural and functional MRI studies suggest a central role for degradation of circuitry originating in the prefrontal cortex including nodes in widespread brain regions. This review features fronto-fugal circuits affected by AUD including frontocerebellar, frontolimbic, and frontostriatal networks and their relations to the salient, enduring, and debilitating cognitive and motor deficits reported in AUD. This article is part of the Special Issue entitled "Alcoholism".

P/Q-type voltage-gated calcium channels mediate the ethanol and CRF sensitivity of central amygdala GABAergic synapses. - Varodayan, FP; Logrip, ML; Roberto, M (Neuropharmacology, 2017)
The central amygdala (CeA) GABAergic system is hypothesized to drive the development of alcohol dependence, due to its pivotal roles in the reinforcing actions of alcohol and the expression of negative emotion, anxiety and stress. Recent work has also identified an important role for the CeA corticotropin-releasing factor (CRF) system in the interaction between anxiety/stress and alcohol dependence. We have previously shown that acute alcohol and CRF each increase action potential-independent GABA release in the CeA via their actions at presynaptic CRF type 1 receptors (CRF1s); however, the shared mechanism employed by these two compounds requires further investigation. Here we report that acute alcohol interacts with the CRF/CRF1 system, such that CRF and alcohol act via presynaptic CRF1s and P/Q-type voltage-gated calcium channels to promote vesicular GABA release and that both compounds occlude the effects of each other at these synapses. Chronic alcohol exposure does not alter P/Q-type voltage-gated calcium channel membrane abundance or this CRF1/P/Q-type voltage-gated calcium channel mechanism of acute alcohol-induced GABA release, indicating that alcohol engages this molecular mechanism at CeA GABAergic synapses throughout the transition to dependence. Thus, P/Q-type voltage-gated calcium channels, like CRF1s, are key regulators of the effects of alcohol on GABAergic signaling in the CeA.

Prefrontal cortex expression of chromatin modifier genes in male WSP and WSR mice changes across ethanol dependence, withdrawal, and abstinence. - Hashimoto JG,; Gavin DP,; Wiren KM,; Crabbe JC,; Guizzetti M. (Alcohol, 2017)
Alcohol-use disorder (AUD) is a relapsing disorder associated with excessive ethanol consumption. Recent studies support the involvement of epigenetic mechanisms in the development of AUD. Studies carried out so far have focused on a few specific epigenetic modifications. The goal of this project was to investigate gene expression changes of epigenetic regulators that mediate a broad array of chromatinmodifications after chronic alcohol exposure, chronic alcohol exposure followed by 8 h withdrawal, and chronic alcohol exposure followed by 21 days of abstinence in Withdrawal-Resistant (WSR) and Withdrawal Seizure-Prone (WSP) selected mouse lines. We found that chronic vapor exposure to highly intoxicating levels of ethanol alters the expression of several chromatin remodeling genes measured by quantitative PCR array analyses. The identified effects were independent of selected lines, which, however, displayed baseline differences in epigenetic gene expression. We reported dysregulation in the expression of genes involved in histone acetylation, deacetylation, lysine and arginine methylation and ubiquitinationhylation during chronic ethanol exposure and withdrawal, but not after 21 days of abstinence. Ethanol-induced changes are consistent with decreased histone acetylation and with decreased deposition of the permissive ubiquitination mark H2BK120ub, associated with reduced transcription. On the other hand, ethanol-induced changes in the expression of genes involved in histone lysine methylation are consistent with increased transcription. The net result of these modifications on gene expression is likely to depend on the combination of the specific histone tail modifications present at a given time on a given promoter. Since alcohol does not modulate gene expression unidirectionally, it is not surprising that alcohol does not unidirectionally alter chromatin structure toward a closed or open state, as suggested by the results of this study.

Rat animal models for screening medications to treat alcohol use disorders. - Bell RL,; Hauser SR,; Liang T,; Sari Y,; Maldonado-Devincci A,; Rodd ZA. (Neuropharmacology, 2017)
The purpose of this review is to present animal research models that can be used to screen and/or repurpose medications for the treatment of alcohol abuse and dependence. The focus will be on rats and in particular selectively bred rats. Brief introductions discuss various aspects of the clinical picture, which provide characteristics of individuals with alcohol use disorders (AUDs) to model in animals. Following this, multiple selectively bred rat lines will be described and evaluated in the context of animal models used to screen medications to treat AUDs. Next, common behavioral tests for drug efficacy will be discussed particularly as they relate to stages in the addiction cycle. Tables highlighting studies that have tested the effects of compounds using the respective techniques are included. Wherever possible the Tables are organized chronologically in ascending order to describe changes in the focus of research on AUDs over time. In general, high ethanol-consuming selectively bred rats have been used to test a wide range of compounds. Older studies usually followed neurobiological findings in the selected lines that supported an association with a propensity for high ethanol intake. Most of these tests evaluated the compound's effects on the maintenance of ethanol drinking. Very few compounds have been tested during ethanol-seeking and/or relapse and fewer still have assessed their effects during the acquisition of AUDs. Overall, while a substantial number of neurotransmitter and neuromodulatory system targets have been assessed; the roles of sex- and age-of-animal, as well as the acquisition of AUDs, ethanol-seeking and relapse continue to be factors and behaviors needing further study. This article is part of the Special Issue entitled "Alcoholism".

Reduced Levels of mGlu2 Receptors within the prelimbic cortex are not associated with elevated glutamate transmission or high alcohol drinking. - Ding ZM,; Ingraham CM,; Hauser SR,; Lasek AW,; Bell RL,; McBride WJ. (Alcoholism: Clinical and Experimental Research, 2017)
BACKGROUND: A Grm2 cys407* stop codon mutation, which results in a loss of the metabotropic glutamate 2 (mGlu2) receptor protein, was identified as being associated with high alcohol drinking by alcohol-preferring (P) rats. The objectives of the current study were to characterize the effects of reduced levels of mGlu2 receptors on glutamate transmission and alcohol drinking. METHODS: Quantitative no-net-flux microdialysis was used to test the hypothesis that basal extracellular glutamate levels in the prelimbic(PL) cortex and nucleus accumbens shell (NACsh) will be higher in P than Wistar rats. A lentiviral-delivered short-hairpin RNA (shRNA)-mediated knockdown was used to test the hypothesis that reduced levels of mGlu2 receptors within the PL cortex will increase voluntary alcohol drinking by Wistar rats. A linear regression analysis was used to test the hypothesis that there will be a significant correlation between the Grm2 cys407* mutation and level of alcohol intake. RESULTS: Extracellular glutamate concentrations within the PL cortex (3.6 ± 0.6 vs. 6.4 ± 0.6 μM) and NACsh (3.2 ± 0.4 vs. 6.6 ± 0.6 μM) were significantly lower in female P than female Wistar rats. Western blot detected the presence of mGlu2 receptors in these regions of female Wistar rats, but not female P rats. Micro-infusion of shRNAs into the PL cortex significantly reduced local mGlu2 receptor levels (by 40%), but did not alter voluntary alcohol drinking in male Wistar rats. In addition, there was no significant correlation between the Grm2 mutation and alcohol intake in 36 rodent lines (r = 0.29, p > 0.05). CONCLUSIONS: Collectively, these results suggest a lack of association between the loss of mGlu2 receptors and glutamate transmission in the NACsh and PL cortex of female P rats, and between the level of mGlu2 receptors in the PL cortex and alcohol drinking of male Wistar rats.

Remodeling of sensorimotor brain connectivity in Gpr88-deficient mice. - Arefin TM,; Mechling AE,; Meirsman AC,; Bienert T,; Hübner NS,; Lee HL,; Ben Hamida S,; Ehrlich A,; Roquet D,; Hennig J,; von Elverfeldt D,; Kieffer BL,; et al. (Brain Connectivity, 2017)
Recent studies have demonstrated that orchestrated gene activity and expression support synchronous activity of brain networks. However, there is a paucity of information on the consequences of single gene function on overall brain functional organization and connectivity and how this translates at the behavioral level. In this study, we combined mouse mutagenesis with functional and structural magnetic resonance imaging (MRI) to determine whether targeted inactivation of a single gene would modify whole-brain connectivity in live animals. The targeted gene encodes GPR88 (G protein-coupled receptor 88), an orphan G protein-coupled receptor enriched in the striatum and previously linked to behavioral traits relevant to neuropsychiatric disorders. Connectivity analysis of Gpr88-deficient mice revealed extensive remodeling of intracortical and cortico-subcortical networks. Most prominent modifications were observed at the level of retrosplenial cortex connectivity, central to the default mode network (DMN) whose alteration is considered a hallmark of many psychiatric conditions. Next, somatosensory and motor cortical networks were most affected. These modifications directly relate to sensorimotor gating deficiency reported in mutant animals and also likely underlie their hyperactivity phenotype. Finally, we identified alterations within hippocampal and dorsal striatum functional connectivity, most relevant to a specific learning deficit that we previously reported in Gpr88-/- animals. In addition, amygdala connectivity with cortex and striatum was weakened, perhaps underlying the risk-taking behavior of these animals. This is the first evidence demonstrating that GPR88 activity shapes the mouse brain functional and structural connectome. The concordance between connectivityalterations and behavior deficits observed in Gpr88-deficient mice suggests a role for GPR88 in brain communication.

Sedative and motor incoordination effects of ethanol in mice lacking CD14, TLR2, TLR4, or MyD88. - Blednov YA,; Black M,; Benavidez JM,; Da Costa A,; Mayfield J,; Harris RA. (Alcoholism: Clinical and Experimental Research, 2017)
BACKGROUND: In our companion article, we examined the role of MyD88-dependent signaling in ethanol (EtOH) consumption in mice lacking key components of this inflammatory pathway and observed differential effects on drinking. Here, we studied the role of these same signaling components in the acute sedative, intoxicating, and physiological effects of EtOH. Toll-like receptor 4 (TLR4) has been reported to strongly reduce the duration of EtOH-induced sedation, although most studies do not support its direct involvement in EtOH consumption. We examined TLR4 and other MyD88 pathway molecules to determine signaling specificity in acute EtOH-related behaviors. We also studied other GABAergic sedatives to gauge the EtOH specificity and potential role for GABA in EtOH's sedative and intoxicating effects in the mutant mice. METHODS: Loss of righting reflex (LORR) and recovery from motor incoordination were studied following acute injection of EtOH or other sedative drugs in male and female control C57BL/6J mice versus mice lacking CD14, TLR2, TLR4 (C57BL/10ScN), or MyD88. We also examined EtOH-induced hypothermia and blood EtOH clearance in these mice. RESULTS: Male and female mice lacking TLR4 or MyD88 showed reduced duration of EtOH-induced LORR and faster recovery from EtOH-induced motor incoordination in the rotarod test. MyD88 knockout mice had slightly faster recovery from EtOH-induced hypothermia compared to control mice. None of the mutants differed from control mice in the rate of blood EtOH clearance. All of the mutants showed similar decreases in the duration of gaboxadol-induced LORR, but only mice lacking TLR4 were less sensitive to the sedative effects of pentobarbital. Faster recovery from diazepam-induced motor impairment was observed in CD14, TLR4, and MyD88 null mice of both sexes. CONCLUSIONS: TLR4 and MyD88 were key mediators of the sedative and intoxicating effects of EtOH and GABAergic sedatives, indicating a strong influence of TLR4-MyD88 signaling on GABAergic function. Despite the involvement of TLR4 in EtOH's acute behaviors, it did not regulate EtOH consumption in any drinking model as shown in our companion article. Collectively, our studies demonstrate differential effects of TLR-MyD88 components in the acute versus chronic actions of EtOH. Copyright © 2017 by the Research Society on Alcoholism

Selective alterations of NMDAR function and plasticity in D1 and D2 medium spiny neurons in the nucleus accumbens shell following chronic intermittent ethanol exposure - Renteria, Rafael; Maier, Esther Y.; Buske, Tavanna R.; Morrisett, Richard A. (Neuropharmacology, 2017)
A major mouse model widely adopted in recent years to induce pronounced ethanol intake is the ethanol vapor model known as "CIE" or "Chronic Intermittent Ethanol." One critical question concerning this model is whether the rapid induction of high blood ethanol levels for such short time periods is sufficient to induce alterations in N-methyl-d-aspartate receptor (NMDAR) function which may contribute to excessive ethanol intake. In this study, we determined whether such short term intermittent ethanol exposure modulates NMDAR function as well as other prominent electrophysiological properties and the expression of plasticity in both D1 (D1+) and D2 (D1-) dopamine receptor expressing medium spiny neurons (MSNs) in the nucleus accumbens (NAc) shell. To distinguish between the two subtypes of MSNs in the NAc we treated Drd1a-TdTomato transgenic mice with CIE vapor and electrophysiological recordings were conducted 24 h after the last vapor exposure. To investigate CIE induced alterations in plasticity, long-term depression (LTD) was induced by pairing low frequency stimulation (LFS) with post synaptic depolarization. In ethanol naïve mice, LFS induced synaptic depression (LTD) was apparent exclusively in D1+ MSNs. Whereas in slices prepared from CIE treated mice, LFS induced synaptic potentiation (LTP) in D1+ MSNs. Furthermore, following CIE exposure, LFS now produced LTD in D1- MSNs. We found that CIE exposure induced an increase in excitability in D1+ MSNs with no change in D1- MSNs. After CIE, we found a significant increase in spontaneous EPSCs (sEPSCs) frequency in D1+ but not D1- MSNs suggesting alterations in baseline α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) mediated signaling. CIE induced changes in NMDAR function were measured using the NMDA/AMPA ratio and input-output curves of isolated NMDAR currents. We observed a significant increase in NMDAR function in D1+ MSNs and a decrease in D1- MSNs after ethanol vapor exposure. The reversal of NMDAR function may account for the CIE induced alterations in the expression of plasticity. The cell type specific alterations in excitatory signaling in the NAc shell may constitute an important neuroadaptation necessary for the expression of increased ethanol consumption induced by intermittent ethanol vapor exposure. This article is part of the Special Issue entitled 'Ionotropic glutamate receptors'.
Keywords: CIE; LTD; LTP; neuroadaptation

Sex differences in responses of the basolateral-central amygdala circuit to alcohol, corticosterone and their interaction - Logrip, Marian L.; Oleata, Christopher; Roberto, Marisa (Neuropharmacology, 2017)
Alcohol use disorders are chronically relapsing conditions that pose significant health challenges for our society. Stress is a prevalent trigger of relapse, particularly for women, yet the mechanisms by which alcohol and stress interact, and how this differs between males and females, remain poorly understood. The glutamatergic circuit connecting the basolateral (BLA) and central (CeA) nuclei of the amygdala is a likely locus for such adaptations, yet the impact of alcohol, corticosterone and their interaction on this circuit has been understudied. In particular, no studies have addressed sex differences in these effects or potential differential responses between the lateral and medial subdivisions of the central nucleus. Thus, we assessed the effects of alcohol and corticosterone treatments on BLA-evoked compound glutamatergic responses in medial and lateral CeA neurons from male and female rats. We observed minimal differences between medial and lateral CeA responses to alcohol and corticosterone in male rats, which were primarily sensitive to alcohol-induced inhibition of glutamatergic postsynaptic potentials. Unlike male neurons, cells from female rats displayed reduced sensitivity to alcohol's inhibitory effects. In addition, female neurons diverged in their sensitivity to corticosterone, with lateral CeA neuronal responses significantly blunted following corticosterone treatment and medial CeA neurons largely unchanged by corticosterone or subsequent co-application of alcohol. Together these data highlight striking differences in how male and female amygdala respond to alcohol and the stress hormone corticosterone, factors which may impact differential susceptibility of the sexes to alcohol- and stress-related disorders.
Keywords: Amygdala; Electrophysiology; Ethanol; Sex differences; Stress

The sodium channel β4 auxiliary subunit selectively controls long-term depression in core nucleus accumbens medium spiny neurons. - Ji X,; Saha S,; Gao G,; Lasek AW,; Homanics GE,; Guildford M,; Tapper AR,; Martin GE. (Frontiers in Cellular Neuroscience, 2017)
Voltage-gated sodium channels are essential for generating the initial rapid depolarization of neuronal membrane potential during action potentials (APs) that enable cell-to-cell communication, the propagation of signals throughout the brain, and the induction of synaptic plasticity. Although all brain neurons express one or several variants coding for the core pore-forming sodium channel α subunit, the expression of the β (β1-4) auxiliary subunits varies greatly. Of particular interest is the β4 subunit, encoded by the Scn4b gene, that is highly expressed in dorsal and ventral (i.e., nucleus accumbens - NAc) striata compared to other brain regions, and that endows sodium channels with unique gating properties. However, its role on neuronal activity, synaptic plasticity, and behaviors related to drugs of abuse remains poorly understood. Combining whole-cell patch-clamp recordings with two-photon calcium imaging in Scn4b knockout (KO) and knockdown mice, we found that Scn4b altered the properties of APs in core accumbens medium spiny neurons (MSNs). These alterations are associated with a reduction of the probability of MSNs to evoke spike-timing-dependent long-term depression (tLTD) and a reduced ability of backpropagating APs to evoke dendritic calcium transients. In contrast, long-term potentiation (tLTP) remained unaffected. Interestingly, we also showed that amphetamine-induced locomotor activity was significantly reduced in male Scn4b KO mice compared to wild-type controls. Taken together, these data indicate that the Scn4b subunit selectively controls tLTD by modulating dendritic calcium transients evoked by backpropagating APs.

Synaptic targets: Chronic alcohol actions - Roberto, M; Varodayan, FP (Neuropharmacology., 2017)
Alcohol acts on numerous cellular and molecular targets to regulate neuronal communication within the brain. Chronic alcohol exposure and acute withdrawal generate prominent neuroadaptations at synapses, including compensatory effects on the expression, localization and function of synaptic proteins, channels and receptors. The present article reviews the literature describing the synaptic effects of chronic alcohol exposure and their relevance for synaptic transmission in the central nervous system. This review is not meant to be comprehensive, but rather to highlight the effects that have been observed most consistently and that are thought to contribute to the development of alcohol dependence and the negative aspects of withdrawal. Specifically, we will focus on the major excitatory and inhibitory neurotransmitters in the brain, glutamate and GABA, respectively, and how their neuroadaptations after chronic alcohol exposure contributes to alcohol reinforcement, dependence and withdrawal. This article is part of the Special Issue entitled "Alcoholism".

Tagging of endogenous BK channels with a fluorogen-activating peptide reveals β4-mediated control of channel clustering in cerebellum - Pratt, CP; Kuljis, DA; Homanics, GE; He, J; Kolodieznyi, D; Dudem, S; Hollywood, MA; Barth, AL; Bruchez, MP (Frontiers in Cellular Neuroscience, 2017)
BK channels are critical regulators of neuronal activity, controlling firing, neurotransmitter release, cerebellar function, and BK channel mutations have been linked to seizure disorders. Modulation of BK channel gating is well characterized, regulated by accessory subunit interactions, intracellular signaling pathways, and membrane potential. In contrast, the role of intracellular trafficking mechanisms in controlling BK channel function, especially in live cells, has been less studied. Fluorogen-activating peptides (FAPs) are well-suited for trafficking and physiological studies due to the binding of malachite green (MG)-based dyes with sub-nanomolar affinity to the FAP, resulting in bright, photostable, far-red fluorescence. Cell-excluded MG dyes enable the selective tagging of surface protein and tracking through endocytic pathways. We used CRISPR to insert the FAP at the extracellular N-terminus of BKα in the first exon of its native locus, enabling regulation by the native promoter elements and tag incorporation into multiple splice isoforms. Motor coordination was found to be normal; however, BK channel expression seems to be reduced in some locations. Alternate start site selection or post-translational proteolytic processing resulted in incomplete FAP tagging of the BKα proteins in brain tissues. In Purkinje cell somata, FAP revealed BK channel clustering previously only observed by electron microscopy. Measurement of these clusters in β4+/- and β4-/- mice showed that puncta number and cluster fluorescence intensity on the soma are reduced in β4-/- knockout animals. This novel mouse line provides a versatile fluorescent platform for studying endogenous BK channels in living and fixed tissues. Future studies could apply this line to ex vivo neuronal cultures to study live-cell channel trafficking.

Transgenic mice with increased astrocyte expression of CCL2 show altered behavioral effects of alcohol. Neuroscience - Bray, JG; Roberts, AJ; Gruol, DL (Neuroscience, 2017)
Emerging research provides strong evidence that activation of CNS glial cells occurs in neurological diseases and brain injury and results in elevated production of neuroimmune factors. These factors can contribute to pathophysiological processes that lead to altered CNS function. Recently, studies have also shown that both acute and chronic alcohol consumption can produce activation of CNS glial cells and the production of neuroimmune factors, particularly the chemokine ligand 2 (CCL2). The consequences of alcohol-induced increases in CCL2 levels in the CNS have yet to be fully elucidated. Our studies focus on the hypothesis that increased levels of CCL2 in the CNS produce neuroadaptive changes that modify the actions of alcohol on the CNS. We utilized behavioral testing in transgenic mice that express elevated levels of CCL2 to test this hypothesis. The increased level of CCL2 in the transgenic mice involves increased astrocyte expression. Transgenic mice and their non-transgenic littermate controls were subjected to one of two alcohol exposure paradigms, a two-bottle choice alcohol drinking procedure that does not produce alcohol dependence or a chronic intermittent alcohol procedure that produces alcohol dependence. Several behavioral tests were carried out including the Barnes maze, Y-maze, cued and contextual conditioned fear test, light-dark transfer, and forced swim test. Comparisons between alcohol naïve, non-dependent, and alcohol-dependent CCL2 transgenic and non-transgenic mice show that elevated levels of CCL2 in the CNS interact with alcohol in tests for alcohol drinking, spatial learning, and associative learning.

Translating the Habenula-From Rodents to Humans - Boulos, Laura-Joy; Darcq, Emmanuel; Kieffer, Brigitte Lina (Biological Psychiatry, 2017)
The habenula (Hb) is a central structure connecting forebrain to midbrain regions. This microstructure regulates monoaminergic systems, notably dopamine and serotonin, and integrates cognitive with emotional and sensory processing. Early preclinical data have described Hb as a brain nucleus activated in anticipation of aversive outcomes. Evidence has now accumulated to show that the Hb encodes both rewarding and aversive aspects of external stimuli, thus driving motivated behaviors and decision making. Human Hb research is still nascent but develops rapidly, alongside with the growth of neuroimaging and deep brain stimulation techniques. Not surprisingly, Hb dysfunction has been associated with psychiatric disorders, and studies in patients have established evidence for Hb involvement in major depression, addiction, and schizophrenia, as well as in pain and analgesia. Here, we summarize current knowledge from animal research and overview the existing human literature on anatomy and function of the Hb. We also discuss challenges and future directions in targeting this small brain structure in both rodents and humans. By combining animal data and human experimental studies, this review addresses the translational potential of preclinical Hb research.
Keywords: addiction; Depression; Habenula; Human; Reward; Rodent

Alcohol consumption induces global gene expression changes in VTA dopaminergic neurons - Marballi, K.; Genabai, N. K.; Blednov, Y. A.; Harris, R. A.; Ponomarev, I. (Genes, Brain, and Behavior, 2016)
Alcoholism is associated with dysregulation in the neural circuitry that mediates motivated and goal-directed behaviors. The dopaminergic (DA) connection between the ventral tegmental area (VTA) and the nucleus accumbens is viewed as a critical component of the neurocircuitry mediating alcohol's rewarding and behavioral effects. We sought to determine the effects of binge alcohol drinking on global gene expression in VTA DA neurons. Alcohol-preferring C57BL/6J × FVB/NJ F1 hybrid female mice were exposed to a modified drinking in the dark (DID) procedure for 3 weeks, while control animals had access to water only. Global gene expression of laser-captured tyrosine hydroxylase (TH)-positive VTA DA neurons was measured using microarrays. A total of 644 transcripts were differentially expressed between the drinking and nondrinking mice, and 930 transcripts correlated with alcohol intake during the last 2 days of drinking in the alcohol group. Bioinformatics analysis of alcohol-responsive genes identified molecular pathways and networks perturbed in DA neurons by alcohol consumption, which included neuroimmune and epigenetic functions, alcohol metabolism and brain disorders. The majority of genes with high and specific expression in DA neurons were downregulated by or negatively correlated with alcohol consumption, suggesting a decreased activity of DA neurons in high drinking animals. These changes in the DA transcriptome provide a foundation for alcohol-induced neuroadaptations that may play a crucial role in the transition to addiction.
Keywords: Addictive; Alcohol consumption; Alcohol Drinking; Animals; Behavior; dopamine; Dopaminergic Neurons; Ethanol; Female; Gene Expression; Gene Expression Regulation; Inbred C57BL; laser capture microdissection; Mice; Microarrays; neuroadaptation; Nucleus Accumbens; Ventral tegmental area

Alcohol enhances unprovoked 22-28 kHz USVs and suppresses USV mean frequency in High Alcohol Drinking (HAD-1) male rats - Thakore, Neha; Reno, James M.; Gonzales, Rueben A.; Schallert, Timothy; Bell, Richard L.; Maddox, W. Todd; Duvauchelle, Christine L. (Behavioural Brain Research, 2016)
Heightened emotional states increase impulsive behaviors such as excessive ethanol consumption in humans. Though positive and negative affective states in rodents can be monitored in real-time through ultrasonic vocalization (USV) emissions, few animal studies have focused on the role of emotional status as a stimulus for initial ethanol drinking. Our laboratory has recently developed reliable, high-speed analysis techniques to compile USV data during multiple-hour drinking sessions. Since High Alcohol Drinking (HAD-1) rats are selectively bred to voluntarily consume intoxicating levels of alcohol, we hypothesized that USVs emitted by HAD-1 rats would reveal unique emotional phenotypes predictive of alcohol intake and sensitive to alcohol experience. In this study, male HAD-1 rats had access to water, 15% and 30% EtOH or water only (i.e., Controls) during 8 weeks of daily 7-h drinking-in-the-dark (DID) sessions. USVs, associated with both positive (i.e., 50-55 kHz frequency-modulated or FM) and negative (i.e., 22-28 kHz) emotional states, emitted during these daily DID sessions were examined. Findings showed basal 22-28 kHz USVs were emitted by both EtOH-Naïve (Control) and EtOH-experienced rats, alcohol experience enhanced 22-28 kHz USV emissions, and USV acoustic parameters (i.e., mean frequency in kHz) of both positive and negative USVs were significantly suppressed by chronic alcohol experience. These data suggest that negative affective status initiates and maintains excessive alcohol intake in selectively bred HAD-1 rats and support the notion that unprovoked emissions of negative affect-associated USVs (i.e., 22-28 kHz) predict vulnerability to excessive alcohol intake in distinct rodent models.
Keywords: Acoustic Stimulation; Acoustics; Alcohol Drinking; Algorithms; Analysis of Variance; Animal; Animals; Central Nervous System Depressants; Dose-Response Relationship; Drinking; Drinking-in-the-dark; Drug; Emotional Status; Ethanol; Excessive Alcohol Intake; Male; Negative Affect; Rats; Reproducibility of Results; Self Administration; Vocalization; WAAVES

BK Channels in the Central Nervous System - Contet, C.; Goulding, S. P.; Kuljis, D. A.; Barth, A. L. (International Review of Neurobiology, 2016)
Large conductance Ca(2+)- and voltage-activated K(+) (BK) channels are widely distributed in the postnatal central nervous system (CNS). BK channels play a pleiotropic role in regulating the activity of brain and spinal cord neural circuits by providing a negative feedback mechanism for local increases in intracellular Ca(2+) concentrations. In neurons, they regulate the timing and duration of K(+) influx such that they can either increase or decrease firing depending on the cellular context, and they can suppress neurotransmitter release from presynaptic terminals. In addition, BK channels located in astrocytes and arterial myocytes modulate cerebral blood flow. Not surprisingly, both loss and gain of BK channel function have been associated with CNS disorders such as epilepsy, ataxia, mental retardation, and chronic pain. On the other hand, the neuroprotective role played by BK channels in a number of pathological situations could potentially be leveraged to correct neurological dysfunction.
Keywords: Action potential; Afterhyperpolarization; alcoholism; Ataxia; BK channels; Brain; Calcium; Circadian Rhythm; Depolarization; Epilepsy; Excitability; Firing; Glaucoma; Ischemia; KCNMA1; Mental retardation; Neurodegeneration; Neurons; Neurotransmission; Neurovascular coupling; Pain; Slo1; Spinal Cord; Transmitter release; Tremor; Waveform

Cell-type-specific tonic GABA signaling in the rat central amygdala is selectively altered by acute and chronic ethanol - Herman, Melissa Ann; Roberto, Marisa (Addiction Biology, 2016)
The central nucleus of the amygdala (CeA) is an important site for the reinforcing effects of ethanol and has been implicated in the development of alcohol dependence. The CeA GABAA receptor system is particularly vulnerable to the effects of acute and chronic ethanol exposure. Previous work in the CeA focused on ethanol and phasic GABAA receptor signaling, but tonic GABAA receptor signaling in the rat CeA remains understudied. In the present study, we found that the CeA contains two types of tonic conductance that are expressed in a cell-type-specific manner. Low threshold bursting (LTB) and some regular spiking (RS) neurons have an ongoing tonic conductance that is mediated by the α1-GABAA receptor subunit and is insensitive to acute ethanol exposure. Late spiking (LS) and a separate population of RS neurons do not display a persistent tonic conductance but have the potential for tonic signaling that is mediated by the δ-GABAA receptor subunit and can be activated by increasing the ambient GABA concentration or by acute ethanol exposure. Acute ethanol exposure differentially alters the firing discharge of different CeA cell types. Chronic ethanol exposure produces a switch in tonic signaling such that the tonic conductance in LTB and some RS neurons is lost and an ongoing tonic conductance is present in LS and a separate population of RS neurons. Collectively, these data demonstrate cell-type-specific tonic signaling in the CeA and provide new insight into how acute and chronic ethanol exposure differentially alter specific aspects of inhibitory circuitry in the CeA.
Keywords: alcohol; Animals; Central Amygdaloid Nucleus; Central Nervous System Depressants; delta; Ethanol; GABA-A; GABAA; gamma-Aminobutyric Acid; Neurons; Patch-Clamp Techniques; Rats; Receptors

Chromatin immunoprecipitation and gene expression analysis of neuronal subtypes after fluorescence activated cell sorting - Finegersh, Andrey; Homanics, Gregg E. (Journal of Neuroscience Methods, 2016)
BACKGROUND: With advances in cell capture, gene expression can now be studied in neuronal subtypes and single cells; however, studying epigenetic mechanisms that underlie these changes presents challenges. Moreover, chromatin immunoprecipitation (ChIP) protocols optimized for low cell number do not adequately address technical issues and cell loss while preparing tissue for fluorescence activated cell sorting (FACS). Developing a reliable FACS-ChIP protocol without the need for pooling tissue from multiple animals would enable study of epigenetic mechanisms in neuronal subtypes. METHODS: FACS was used to isolate dopamine 1 receptor (D1R) expressing cells from the nucleus accumbens (NAc) of a commercially available BAC transgenic mouse strain. D1R+ cells were used to study gene expression as well as histone modifications at gene promoters using a novel native ChIP protocol. RESULTS: Isolated cells had enrichment of the dopamine 1 receptor (D1R) mRNA and nearly undetectable levels of GFAP and D2R mRNA. ChIP analysis demonstrated the association of activating or repressive histone modifications with highly expressed or silent gene promoters, respectively. COMPARISON WITH EXISTING METHODS: The ChIP protocol developed in this paper enables characterization of histone modifications from ∼30,000 FAC-sorted neurons. CONCLUSIONS: We describe a one day FACS-ChIP protocol that can be applied to epigenetic studies of neuronal subtypes without pooling tissue.
Keywords: Animals; Chromatin Immunoprecipitation; Dopamine D1; Epigenesis; Epigenetics; Flow Cytometry; Fluorescence activated cell sorting; Genetic; Glial Fibrillary Acidic Protein; Histone acetylation; Histone methylation; Histones; Inbred C57BL; Luminescent Proteins; Male; Messenger; Mice; Neurons; Nucleus Accumbens; Receptors; RNA; Transgenic

Chronic ethanol exposure decreases CB1 receptor function at GABAergic synapses in the rat central amygdala - Varodayan, Florence P.; Soni, Neeraj; Bajo, Michal; Luu, George; Madamba, Samuel G.; Schweitzer, Paul; Parsons, Loren H.; Roberto, Marisa (Addiction Biology, 2016)
The endogenous cannabinoids (eCBs) influence the acute response to ethanol and the development of tolerance, dependence and relapse. Chronic alcohol exposure alters eCB levels and Type 1 cannabinoid receptor (CB1 ) expression and function in brain regions associated with addiction. CB1 inhibits GABA release, and GABAergic dysregulation in the central nucleus of the amygdala (CeA) is critical in the transition to alcohol dependence. We investigated possible disruptions in CB1 signaling of rat CeA GABAergic transmission following intermittent ethanol exposure. In the CeA of alcohol-naive rats, CB1 agonist WIN 55,212-2 (WIN) decreased the frequency of spontaneous and miniature GABAA receptor-mediated inhibitory postsynaptic currents (s/mIPSCs). This effect was prevented by CB1 antagonism, but not Type 2 cannabinoid receptor (CB2 ) antagonism. After 2-3 weeks of intermittent ethanol exposure, these WIN inhibitory effects were attenuated, suggesting ethanol-induced impairments in CB1 function. The CB1 antagonist AM251 revealed a tonic eCB/CB1 control of GABAergic transmission in the alcohol-naive CeA that was occluded by calcium chelation in the postsynaptic cell. Chronic ethanol exposure abolished this tonic CB1 influence on mIPSC, but not sIPSC, frequency. Finally, acute ethanol increased CeA GABA release in both naive and ethanol-exposed rats. Although CB1 activation prevented this effect, the AM251- and ethanol-induced GABA release were additive, ruling out a direct participation of CB1 signaling in the ethanol effect. Collectively, these observations demonstrate an important CB1 influence on CeA GABAergic transmission and indicate that the CeA is particularly sensitive to alcohol-induced disruptions of CB1 signaling.
Keywords: alcohol; Amygdala; cannabinoid; endocannabinoid CB1 receptor; GABA

Concomitants of alcoholism: differential effects of thiamine deficiency, liver damage, and food deprivation on the rat brain in vivo - Zahr, Natalie M.; Sullivan, Edith V.; Rohlfing, Torsten; Mayer, Dirk; Collins, Amy M.; Luong, Richard; Pfefferbaum, Adolf (Psychopharmacology, 2016)
RATIONALE: Serious neurological concomitants of alcoholism include Wernicke's encephalopathy (WE), Korsakoff's syndrome (KS), and hepatic encephalopathy (HE). OBJECTIVES: This study was conducted in animal models to determine neuroradiological signatures associated with liver damage caused by carbon tetrachloride (CCl4), thiamine deficiency caused by pyrithiamine treatment, and nonspecific nutritional deficiency caused by food deprivation. METHODS: Magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) were used to evaluate brains of wild-type Wistar rats at baseline and following treatment. RESULTS: Similar to observations in ethanol (EtOH) exposure models, thiamine deficiency caused enlargement of the lateral ventricles. Liver damage was not associated with effects on cerebrospinal fluid volumes, whereas food deprivation caused modest enlargement of the cisterns. In contrast to what has repeatedly been shown in EtOH exposure models, in which levels of choline-containing compounds (Cho) measured by MRS are elevated, Cho levels in treated animals in all three experiments (i.e., liver damage, thiamine deficiency, and food deprivation) were lower than those in baseline or controls. CONCLUSIONS: These results add to the growing body of literature suggesting that MRS-detectable Cho is labile and can depend on a number of variables that are not often considered in human experiments. These results also suggest that reductions in Cho observed in humans with alcohol use disorder (AUD) may well be due to mild manifestations of concomitants of AUD such as liver damage or nutritional deficiencies and not necessarily to alcohol consumption per se.
Keywords: Carbon tetrachloride; Hematology; Magnetic resonance; Pyrithiamine; Spectroscopy

Concomitants of alcoholism: differential effects of thiamine deficiency, liver damage, and food deprivation on the rat brain in vivo - Zahr, Natalie M.; Sullivan, Edith V.; Rohlfing, Torsten; Mayer, Dirk; Collins, Amy M.; Luong, Richard; Pfefferbaum, Adolf (Psychopharmacology, 2016)
RATIONALE: Serious neurological concomitants of alcoholism include Wernicke's encephalopathy (WE), Korsakoff's syndrome (KS), and hepatic encephalopathy (HE). OBJECTIVES: This study was conducted in animal models to determine neuroradiological signatures associated with liver damage caused by carbon tetrachloride (CCl4), thiamine deficiency caused by pyrithiamine treatment, and nonspecific nutritional deficiency caused by food deprivation. METHODS: Magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) were used to evaluate brains of wild-type Wistar rats at baseline and following treatment. RESULTS: Similar to observations in ethanol (EtOH) exposure models, thiamine deficiency caused enlargement of the lateral ventricles. Liver damage was not associated with effects on cerebrospinal fluid volumes, whereas food deprivation caused modest enlargement of the cisterns. In contrast to what has repeatedly been shown in EtOH exposure models, in which levels of choline-containing compounds (Cho) measured by MRS are elevated, Cho levels in treated animals in all three experiments (i.e., liver damage, thiamine deficiency, and food deprivation) were lower than those in baseline or controls. CONCLUSIONS: These results add to the growing body of literature suggesting that MRS-detectable Cho is labile and can depend on a number of variables that are not often considered in human experiments. These results also suggest that reductions in Cho observed in humans with alcohol use disorder (AUD) may well be due to mild manifestations of concomitants of AUD such as liver damage or nutritional deficiencies and not necessarily to alcohol consumption per se.
Keywords: Carbon tetrachloride; Hematology; Magnetic resonance; Pyrithiamine; Spectroscopy

Defining the role of corticotropin releasing factor binding protein in alcohol consumption - Haass-Koffler, C. L.; Henry, A. T.; Melkus, G.; Simms, J. A.; Naemmuddin, M.; Nielsen, C. K.; Lasek, A. W.; Magill, M.; Schwandt, M. L.; Momenan, R.; Hodgkinson, C. A.; Bartlett, S. E.; et al. (Translational Psychiatry, 2016)
The corticotropin releasing factor (CRF) exerts its effects by acting on its receptors and on the binding protein (CRFBP), and has been implicated in alcohol use disorder (AUD). Therefore, identification of the exact contribution of each protein that mediates CRF effects is necessary to design effective therapeutic strategies for AUD. A series of in vitro/in vivo experiments across different species were performed to define the biological discrete role of CRFBP in AUD. First, to establish the CRFBP role in receptor signaling, we developed a novel chimeric cell-based assay and showed that CFRBP full length can stably be expressed on the plasma membrane. We discovered that only CRFBP(10 kD) fragment is able to potentiate CRF-intracellular Ca(2+) release. We provide evidence that CRHBP gene loss increased ethanol consumption in mice. Then, we demonstrate that selective reduction of CRHBP expression in the center nucleus of the amygdala (CeA) decreases ethanol consumption in ethanol-dependent rats. CRFBP amygdalar downregulation, however, does not attenuate yohimbine-induced ethanol self-administration. This effect was associated with decreased hemodynamic brain activity in the CRFBP-downregulated CeA and increased hemodynamic activity in the caudate putamen during yohimbine administration. Finally, in alcohol-dependent patients, genetic variants related to the CRFBP(10 kD) fragment were associated with greater risk for alcoholism and anxiety, while other genetic variants were associated with reduced risk for anxiety. Taken together, our data provide evidence that CRFBP may possess both inhibitory and excitatory roles and may represent a novel pharmacological target for the treatment of AUD.

Deletion of the mu opioid receptor gene in mice reshapes the reward-aversion connectome - Mechling, Anna E.; Arefin, Tanzil; Lee, Hsu-Lei; Bienert, Thomas; Reisert, Marco; Ben Hamida, Sami; Darcq, Emmanuel; Ehrlich, Aliza; Gaveriaux-Ruff, Claire; Parent, Maxime J.; Rosa-Neto, Pedro; Hennig, Jürgen; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Connectome genetics seeks to uncover how genetic factors shape brain functional connectivity; however, the causal impact of a single gene's activity on whole-brain networks remains unknown. We tested whether the sole targeted deletion of the mu opioid receptor gene (Oprm1) alters the brain connectome in living mice. Hypothesis-free analysis of combined resting-state fMRI diffusion tractography showed pronounced modifications of functional connectivity with only minor changes in structural pathways. Fine-grained resting-state fMRI mapping, graph theory, and intergroup comparison revealed Oprm1-specific hubs and captured a unique Oprm1 gene-to-network signature. Strongest perturbations occurred in connectional patterns of pain/aversion-related nodes, including the mu receptor-enriched habenula node. Our data demonstrate that the main receptor for morphine predominantly shapes the so-called reward/aversion circuitry, with major influence on negative affect centers.
Keywords: Diffusion Tensor Imaging; mouse brain connectivity; mu opioid receptor; resting-state functional MRI; reward/aversion network

Dependence-induced ethanol drinking and GABA neurotransmission are altered in Alk deficient mice - Schweitzer, Paul; Cates-Gatto, Chelsea; Varodayan, Florence P.; Nadav, Tali; Roberto, Marisa; Lasek, Amy W.; Roberts, Amanda J. (Neuropharmacology, 2016)
Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase that is expressed in the brain and implicated in alcohol abuse in humans and behavioral responses to ethanol in mice. Previous studies have shown an association of human ALK with acute responses to alcohol and alcohol dependence. In addition, Alk knockout (Alk -/-) mice consume more ethanol in a binge-drinking test and show increased sensitivity to ethanol sedation. However, the function of ALK in excessive drinking following the establishment of ethanol dependence has not been examined. In this study, we tested Alk -/- mice for dependence-induced drinking using the chronic intermittent ethanol-two bottle choice drinking (CIE-2BC) protocol. We found that Alk -/- mice initially consume more ethanol prior to CIE exposure, but do not escalate ethanol consumption after exposure, suggesting that ALK may promote the escalation of drinking after ethanol dependence. To determine the mechanism(s) responsible for this behavioral phenotype we used an electrophysiological approach to examine GABA neurotransmission in the central nucleus of the amygdala (CeA), a brain region that regulates alcohol consumption and shows increased GABA signaling after chronic ethanol exposure. GABA transmission in ethanol-naïve Alk -/- mice was enhanced at baseline and potentiated in response to acute ethanol application when compared to wild-type (Alk +/+) mice. Moreover, basal GABA transmission was not elevated by CIE exposure in Alk -/- mice as it was in Alk +/+ mice. These data suggest that ALK plays a role in dependence-induced drinking and the regulation of presynaptic GABA release in the CeA.
Keywords: addiction; ALK; Amygdala; Chronic intermittent ethanol; GABA; Synaptic

Diversity Outbred Mice at 21: Maintaining Allelic Variation in the Face of Selection - Chesler, Elissa J.; Gatti, Daniel M.; Morgan, Andrew P.; Strobel, Marge; Trepanier, Laura; Oberbeck, Denesa; McWeeney, Shannon; Hitzemann, Robert; Ferris, Martin; McMullan, Rachel; Clayshultle, Amelia; Bell, Timothy A.; et al. (G3 (Bethesda, Md.), 2016)
Multi-parent populations (MPPs) capture and maintain the genetic diversity from multiple inbred founder strains to provide a resource for high-resolution genetic mapping through the accumulation of recombination events over many generations. Breeding designs that maintain a large effective population size with randomized assignment of breeders at each generation can minimize the impact of selection, inbreeding, and genetic drift on allele frequencies. Small deviations from expected allele frequencies will have little effect on the power and precision of genetic analysis, but a major distortion could result in reduced power and loss of important functional alleles. We detected strong transmission ratio distortion in the Diversity Outbred (DO) mouse population on chromosome 2, caused by meiotic drive favoring transmission of the WSB/EiJ allele at the R2d2 locus. The distorted region harbors thousands of polymorphisms derived from the seven non-WSB founder strains and many of these would be lost if the sweep was allowed to continue. To ensure the utility of the DO population to study genetic variation on chromosome 2, we performed an artificial selection against WSB/EiJ alleles at the R2d2 locus. Here, we report that we have purged the WSB/EiJ allele from the drive locus while preserving WSB/EiJ alleles in the flanking regions. We observed minimal disruption to allele frequencies across the rest of the autosomal genome. However, there was a shift in haplotype frequencies of the mitochondrial genome and an increase in the rate of an unusual sex chromosome aneuploidy. The DO population has been restored to genome-wide utility for genetic analysis, but our experience underscores that vigilant monitoring of similar genetic resource populations is needed to ensure their long-term utility.
Keywords: aneuploidy; meiotic drive; Multiparent Advanced Generation Inter-Cross (MAGIC); multiparental populations MPP; transmission ratio distortion

Effects of acute alcohol withdrawal on nest building in mice selectively bred for alcohol withdrawal severity. - Greenberg GD,; Phillips TJ,; Crabbe JC, (Physiology and Behavior, 2016)
Nest building has been used to assess thermoregulatory behavior and positive motivational states in mice. There are known genetic influences on ethanol withdrawal severity as well as individual/thermoregulatory nest building. Withdrawal Seizure-Prone (WSP-1, WSP-2) and Withdrawal Seizure-Resistant (WSR-1, WSR-2) mice were selectively bred for high vs low handling-induced convulsion (HIC) severity, respectively, during withdrawal from chronic ethanol vapor inhalation. They also differ in HIC severity during withdrawal from an acute, 4g/kg ethanol injection. In our initial study, withdrawal from an acute dose of ethanol dose-dependently impaired nest building over the initial 24h of withdrawal in genetically segregating Withdrawal Seizure Control (WSC) mice. In two further studies, acute ethanol withdrawal suppressed nest building for up to two days in WSP-1 females. Deficits in nest building from ethanol were limited to the initial 10h of withdrawal in WSR-1 females and to the initial 24h of withdrawal in WSP-1 and WSR-1 males. Effects of ethanol on nest building for up to two days were found in WSP-2 and WSR-2 mice of both sexes. Nest building deficits in female mice from the first replicate could not be explained by a general decrease in locomotor behavior. These results suggest that nest building is a novel behavioral phenotype for indexing the severity of acuteethanol withdrawal, and that genes contributing to this trait differ from those affecting acute withdrawal HIC severity.

Effects of ceftriaxone on ethanol, nicotine or sucrose intake by alcohol-preferring (P) rats and its association with GLT-1 expression - Sari, Youssef; Toalston, Jamie E.; Rao, P. S. S.; Bell, Richard L. (Neuroscience, 2016)
Increased glutamatergic neurotransmission appears to mediate the reinforcing properties of drugs of abuse, including ethanol (EtOH). We have shown that administration of ceftriaxone (CEF), a β-lactam antibiotic, reduced EtOH intake and increased glutamate transporter 1 (GLT-1) expression in mesocorticolimbic regions of male and female alcohol-preferring (P) rats. In the present study, we tested whether CEF administration would reduce nicotine (NIC) and/or EtOH intake by adult female P rats. P rats were randomly assigned to 4 groups: (a) 5% sucrose (SUC) or 10% SUC [SUC], (b) 5% SUC+0.07mg/ml NIC and 10% SUC+0.14mg/ml NIC [NIC-SUC], 15% EtOH and 30% EtOH [EtOH] and (d) 15% EtOH+0.07mg/ml NIC and 30% EtOH+0.14mg/ml NIC [NIC-EtOH]. After achieving stable intakes (4weeks), the rats were administered 7 consecutive, daily i.p. injections of either saline or 200mg/kg CEF. The effects of CEF on intake were significant but differed across the reinforcers; such that ml/kg/day SUC was reduced by ∼30%, mg/kg/day NIC was reduced by ∼70% in the NIC-SUC group and ∼40% in the EtOH-NIC group, whereas g/kg/day EtOH was reduced by ∼40% in both the EtOH and EtOH-NIC group. The effects of CEF on GLT-1 expression were also studied. We found that CEF significantly increased GLT-1 expression in the prefrontal cortex and the nucleus accumbens of the NIC and NIC-EtOH rats as compared to NIC and NIC-EtOH saline-treated rats. These findings provide further support for GLT-1-associated mechanisms in EtOH and/or NIC abuse. The present results along with previous reports of CEF's efficacy in reducing cocaine self-administration in rats suggest that modulation of GLT-1 expression and/or activity is an important pharmacological target for treating polysubstance abuse and dependence.
Keywords: addiction; alcohol; Ceftriaxone; Drinking; EAAT2; polysubstance

Effects of Ethanol on Brain Extracellular Matrix: Implications for Alcohol Use Disorder - Lasek, Amy W. (Alcoholism, Clinical and Experimental Research, 2016)
The brain extracellular matrix (ECM) occupies the space between cells and is involved in cell-matrix and cell-cell adhesion. However, in addition to providing structural support to brain tissue, the ECM activates cell signaling and controls synaptic transmission. The expression and activity of brain ECM components are regulated by alcohol exposure. This review will discuss what is currently known about the effects of alcohol on the activity and expression of brain ECM components. An interpretation of how these changes might promote alcohol use disorder (AUD) will be also provided. Ethanol (EtOH) exposure decreases levels of structural proteins involved in the interstitial matrix and basement membrane, with a concomitant increase in proteolytic enzymes that degrade these components. In contrast, EtOH exposure generally increases perineuronal net components. Because the ECM has been shown to regulate both synaptic plasticity and behavioral responses to drugs of abuse, regulation of the brain ECM by alcohol may be relevant to the development of alcoholism. Although investigation of the function of brain ECM in alcohol abuse is still in early stages, a greater understanding of the interplay between ECM and alcohol might lead to novel therapeutic strategies for treating AUD.
Keywords: Extracellular Matrix; Matrix Metalloproteinases; Perineuronal Nets; synaptic plasticity; Tissue Plasminogen Activator

Effects of isoflurane and ethanol administration on c-Fos immunoreactivity in mice - Smith, M. L.; Li, J.; Cote, D. M.; Ryabinin, A. E. (Neuroscience, 2016)
Noninvasive functional imaging holds great promise for the future of translational research, due to the ability to directly compare between preclinical and clinical models of psychiatric disorders. Despite this potential, concerns have been raised regarding the necessity to anesthetize rodent and monkey subjects during these procedures, because anesthetics may alter neuronal activity. For example, in studies on drugs of abuse and alcohol, it is not clear to what extent anesthesia can interfere with drug-induced neural activity. Therefore, the current study investigated whole-brain c-Fos activation following isoflurane anesthesia as well as ethanol-induced activation of c-Fos in anesthetized mice. In the first experiment, we examined effects of one or three sessions of gaseous isoflurane on c-Fos activation across the brain in male C57BL/6J mice. Isoflurane administration led to c-Fos activation in several areas, including the piriform cortex and lateral septum. Lower or similar levels of activation in these areas were detected after three sessions of isoflurane, suggesting that multiple exposures may eliminate some of the enhanced neuronal activation caused by acute isoflurane. In the second experiment, we investigated the ability of ethanol injection (1.5 or 2.5g/kgi.p.) to induce c-Fos activation under anesthesia. Following three sessions of isoflurane, 1.5g/kg of ethanol induced c-Fos in the central nucleus of amygdala and the centrally-projecting Edinger-Westphal nucleus (EWcp). This induction was lower after 2.5g/kg of ethanol. These results demonstrate that ethanol-induced neural activation can be detected in the presence of isoflurane anesthesia. They also suggest, that while habituation to isoflurane helps reduce neuronal activation, interaction between effects of anesthesia and alcohol can occur. Studies using fMRI imaging could benefit from using habituated animals and dose-response analyses.
Keywords: alcohol; Analysis of Variance; Anesthesia; Anesthetics; Animals; Brain; c-Fos; Central Nervous System Depressants; Ethanol; Gene Expression Regulation; Inbred C57BL; Isoflurane; Male; Mice; Proto-Oncogene Proteins c-fos

Ethanol-Associated Changes in Glutamate Reward Neurocircuitry: A Minireview of Clinical and Preclinical Genetic Findings - Bell, Richard L.; Hauser, Sheketha R.; McClintick, Jeanette; Rahman, Shafiqur; Edenberg, Howard J.; Szumlinski, Karen K.; McBride, William J. (Progress in Molecular Biology and Translational Science, 2016)
Herein, we have reviewed the role of glutamate, the major excitatory neurotransmitter in the brain, in a number of neurochemical, -physiological, and -behavioral processes mediating the development of alcohol dependence. The findings discussed include results from both preclinical as well as neuroimaging and postmortem clinical studies. Expression levels for a number of glutamate-associated genes and/or proteins are modulated by alcohol abuse and dependence. These changes in expression include metabotropic receptors and ionotropic receptor subunits as well as different glutamate transporters. Moreover, these changes in gene expression parallel the pharmacologic manipulation of these same receptors and transporters. Some of these gene expression changes may have predated alcohol abuse and dependence because a number of glutamate-associated polymorphisms are related to a genetic predisposition to develop alcohol dependence. Other glutamate-associated polymorphisms are linked to age at the onset of alcohol-dependence and initial level of response/sensitivity to alcohol. Finally, findings of innate and/or ethanol-induced glutamate-associated gene expression differences/changes observed in a genetic animal model of alcoholism, the P rat, are summarized. Overall, the existing literature indicates that changes in glutamate receptors, transporters, enzymes, and scaffolding proteins are crucial for the development of alcohol dependence and there is a substantial genetic component to these effects. This indicates that continued research into the genetic underpinnings of these glutamate-associated effects will provide important novel molecular targets for treating alcohol abuse and dependence.
Keywords: addiction; alcohol nonpreferring; alcohol preferring; alcoholism; Animals; Brain; Ethanol; family history; genes and environment; Genetics; glutamate system; Glutamic Acid; Humans; Pharmacogenetics; pharmacogenomics; predisposition; Selective breeding

Evaluation of TLR4 Inhibitor, T5342126, in Modulation of Ethanol-Drinking Behavior in Alcohol-Dependent Mice - Bajo, M.; Montgomery, S. E.; Cates, L. N.; Nadav, T.; Delucchi, A. M.; Cheng, K.; Yin, H.; Crawford, E. F.; Roberts, A. J.; Roberto, M. (Alcohol and Alcoholism (Oxford, Oxfordshire), 2016)
AIMS: Several lines of evidence support a critical role of TLR4 in the neuroimmune responses associated with alcohol disorders and propose inhibitors of TLR4 signaling as potential treatments for alcoholism. In this work, we investigated the effect of T5342126 compound, a selective TLR4 inhibitor, on excessive drinking and microglial activation associated with ethanol dependence. METHODS: We used 2BC-CIE (two-bottle choice-chronic ethanol intermittent vapor exposure) paradigm to induce ethanol dependence in mice. After induction of the ethanol dependence, we injected T5342126 (i.p., 57 mg/kg) for 14 days while monitoring ethanol intake by 2BC (limited access to ethanol) method. RESULTS: T5342126 decreased ethanol drinking in both ethanol-dependent and non-dependent mice but T5342126 showed also dose-dependent non-specific effects represented by decreased animal locomotor activity, saccharine intake, and body core temperature. Six days after the last ethanol-drinking session, we examined the immunohistochemical staining of Iba-1 (ionized calcium-binding adapter molecule 1), a microglial activation marker, in the central nucleus of the amygdala (CeA) and dentate gyrus (DG) of the hippocampus. Notably, T5342126 reduced Iba-1 density in the CeA of both ethanol-dependent and non-dependent mice injected with T5342126. There were no significant differences in the DG Iba-1 density among the treatment groups. CONCLUSIONS: Collectively, our data suggest that T5342126, via blocking TLR4 activation, contributes to the reduction of ethanol drinking and ethanol-induced neuroimmune responses. However, the non-specific effects of T5342126 may play a significant role in the T5342126 effects on ethanol drinking and thus, may limit its therapeutic potential for treatment of alcohol dependence. SHORT SUMMARY: T5342126, an experimental TLR4 inhibitor, is effective in reducing ethanol drinking and inhibiting the activation and proliferation of microglia in both ethanol-dependent and non-dependent mice. However, T5342126's use as a potential candidate for the treatment of alcohol addiction may be limited due to its non-specific effects.
Keywords: Alcohol Drinking; alcoholism; Amygdala; Animals; Body Temperature; Calcium-Binding Proteins; Dentate Gyrus; Dose-Response Relationship; Drug; Inbred C57BL; Male; Mice; Microfilament Proteins; Microglia; Motor Activity; Neuroimmunomodulation; Propanolamines; Pyrazoles; Toll-Like Receptor 4

Fear conditioning in mouse lines genetically selected for binge-like ethanol drinking - Crabbe, John C.; Schlumbohm, Jason P.; Hack, Wyatt; Barkley-Levenson, Amanda M.; Metten, Pamela; Lattal, K. Matthew (Alcohol (Fayetteville, N.Y.), 2016)
The comorbidity of substance- and alcohol-use disorders (AUD) with other psychiatric conditions, especially those related to stress such as post-traumatic stress disorder (PTSD), is well-established. Binge-like intoxication is thought to be a crucial stage in the development of the chronic relapsing nature of the addictions, and self-medication through binge-like drinking is commonly seen in PTSD patients. We have selectively bred two separate High Drinking in the Dark (HDID-1 and HDID-2) mouse lines to reach high blood ethanol concentrations (BECs) after a 4-h period of access to 20% ethanol starting shortly after the onset of circadian dark. As an initial step toward the eventual goal of employing binge-prone HDID mice to study PTSD-like behavior including alcohol binge drinking, we sought first to determine their ability to acquire conditioned fear. We asked whether these mice acquired, generalized, or extinguished conditioned freezing to a greater or lesser extent than unselected control HS/Npt mice. In two experiments, we trained groups of 16 adult male mice in a standard conditioned fear protocol. Mice were tested for context-elicited freezing, and then, in a novel context, for cue-induced freezing. After extinction tests, renewal of conditioned fear was tested in the original context. Mice of all three genotypes showed typical fear responding. Context paired with shock elicited freezing behavior in a control experiment, but cue unpaired with shock did not. These studies indicate that fear learning per se does not appear to be influenced by genes causing predisposition to binge drinking, suggesting distinct neural mechanisms. However, HDID mice are shown to be a suitable model for studying the role of conditioned fear specifically in binge-like drinking.
Keywords: Conditioned fear; Drinking in the dark; Ethanol binge drinking; Genetics; Mouse; Selective breeding

FMRP regulates an ethanol-dependent shift in GABABR function and expression with rapid antidepressant properties - Wolfe, Sarah A.; Workman, Emily R.; Heaney, Chelcie F.; Niere, Farr; Namjoshi, Sanjeev; Cacheaux, Luisa P.; Farris, Sean P.; Drew, Michael R.; Zemelman, Boris V.; Harris, R. Adron; Raab-Graham, Kimberly F. (Nature Communications, 2016)
Alcohol promotes lasting neuroadaptive changes that may provide relief from depressive symptoms, often referred to as the self-medication hypothesis. However, the molecular/synaptic pathways that are shared by alcohol and antidepressants are unknown. In the current study, acute exposure to ethanol produced lasting antidepressant and anxiolytic behaviours. To understand the functional basis of these behaviours, we examined a molecular pathway that is activated by rapid antidepressants. Ethanol, like rapid antidepressants, alters γ-aminobutyric acid type B receptor (GABABR) expression and signalling, to increase dendritic calcium. Furthermore, new GABABRs are synthesized in response to ethanol treatment, requiring fragile-X mental retardation protein (FMRP). Ethanol-dependent changes in GABABR expression, dendritic signalling, and antidepressant efficacy are absent in Fmr1-knockout (KO) mice. These findings indicate that FMRP is an important regulator of protein synthesis following alcohol exposure, providing a molecular basis for the antidepressant efficacy of acute ethanol exposure.

A Functional Switch in Tonic GABA Currents Alters the Output of Central Amygdala Corticotropin Releasing Factor Receptor-1 Neurons Following Chronic Ethanol Exposure - Herman, Melissa A.; Contet, Candice; Roberto, Marisa (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2016)
The corticotropin releasing factor (CRF) system in the central amygdala (CeA) has been implicated in the effects of acute ethanol and the development of alcohol dependence. We previously demonstrated that CRF receptor 1 (CRF1) neurons comprise a specific component of the CeA microcircuitry that is selectively engaged by acute ethanol. To investigate the impact of chronic ethanol exposure on inhibitory signaling in CRF1+ CeA neurons, we used CRF1:GFP mice subjected to chronic intermittent ethanol (CIE) inhalation and examined changes in local inhibitory control, the effects of acute ethanol, and the output of these neurons from the CeA. Following CIE, CRF1+ neurons displayed decreased phasic inhibition and a complete loss of tonic inhibition that persisted into withdrawal. CRF1- neurons showed a cell type-specific upregulation of both phasic and tonic signaling with CIE, the latter of which persists into withdrawal and is likely mediated by δ subunit-containing GABAA receptors. The loss of tonic inhibition with CIE was seen in CRF1+ and CRF1- neurons that project out of the CeA and into the bed nucleus of the stria terminalis. CRF1+ projection neurons displayed an increased baseline firing rate and loss of sensitivity to acute ethanol following CIE. These data demonstrate that chronic ethanol exposure produces profound and long-lasting changes in local inhibitory control of the CeA, resulting in an increase in the output of the CeA and the CRF1 receptor system, in particular. These cellular changes could underlie the behavioral manifestations of alcohol dependence and potentially contribute to the pathology of addiction. SIGNIFICANCE STATEMENT: The corticotropin releasing factor (CRF) system in the central amygdala (CeA) has been implicated in the effects of acute and chronic ethanol. We showed previously that CRF receptor 1-expressing (CRF1+) neurons in the CeA are under tonic inhibitory control and are differentially regulated by acute ethanol (Herman et al., 2013). Here we show that the inhibitory control of CRF1+ CeA neurons is lost with chronic ethanol exposure, likely by a functional switch in local tonic signaling. The loss of tonic inhibition is seen in CRF1+ projection neurons, suggesting that a critical consequence of chronic ethanol exposure is an increase in the output of the CeA CRF1 system, a neuroadaptation that may contribute to the behavioral consequences of alcohol dependence.
Keywords: alcohol; Amygdala; CRF; CRF1; GABA; tonic

Gene Expression Changes in Glutamate and GABA-A Receptors, Neuropeptides, Ion Channels, and Cholesterol Synthesis in the Periaqueductal Gray Following Binge-Like Alcohol Drinking by Adolescent Alcohol-Preferring (P) Rats - McClintick, Jeanette N.; McBride, William J.; Bell, Richard L.; Ding, Zheng-Ming; Liu, Yunlong; Xuei, Xiaoling; Edenberg, Howard J. (Alcoholism, Clinical and Experimental Research, 2016)
BACKGROUND: Binge drinking of alcohol during adolescence is a serious public health concern with long-term consequences, including increased pain, fear, and anxiety. The periaqueductal gray (PAG) is involved in processing pain, fear, and anxiety. The effects of adolescent binge drinking on gene expression in this region have yet to be studied. METHODS: Male adolescent alcohol-preferring (P) rats were exposed to repeated binge drinking (three 1-hour sessions/d during the dark/cycle, 5 days/wk for 3 weeks starting at 28 days of age; ethanol intakes of 2.5 to 3 g/kg/session). We used RNA sequencing to assess the effects of ethanol intake on gene expression. RESULTS: Ethanol significantly altered the expression of 1,670 of the 12,123 detected genes: 877 (53%) decreased. In the glutamate system, 23 genes were found to be altered, including reduction in 7 of 10 genes for metabotropic and NMDA receptors. Subunit changes in the NMDA receptor may make it less sensitive to ethanol. Changes in GABAA genes would most likely increase the ability of the PAG to produce tonic inhibition. Five serotonin receptor genes, 6 acetylcholine receptor genes, and 4 glycine receptor genes showed decreased expression in the alcohol-drinking rats. Opioid genes (e.g., Oprk1, Oprm1) and genes for neuropeptides linked to anxiety and panic behaviors (e.g., Npy1r) had mostly decreased expression. Genes for 27 potassium, 10 sodium, and 5 calcium ion channels were found to be differentially expressed. Nine genes in the cholesterol synthesis pathway had decreased expression, including Hmgcr, encoding the rate-limiting enzyme. Genes involved in the production of myelin also had decreased expression. CONCLUSIONS: The results demonstrate that binge alcohol drinking during adolescence produces developmental changes in the expression of key genes within the PAG; many of these changes point to increased susceptibility to pain, fear, and anxiety, which could contribute to excessive drinking to relieve these negative effects.
Keywords: Adolescent binge drinking; alcoholism; Anxiety; Brain; Cholesterol

Gene Targeting Studies of Hyperexcitability and Affective States of Alcohol Withdrawal in Rodents - Greenberg, G. D.; Crabbe, J. C. (International Review of Neurobiology, 2016)
Genetically engineered rodents can be used to examine the influence of single genes on alcoholism-related phenotypes. We review studies that employed gene targeting with a focus on ethanol withdrawal-associated behaviors. Earlier studies targeted the glutamate and GABA systems as contributors to the underlying hyperexcitable state of convulsions or similar signs of ethanol withdrawal. Over the past decade, many gene-targeting studies have continued to focus on the glutamatergic and GABAergic systems; however, an increasing number of these studies have focused on other withdrawal outcomes such as anxiety-like behavior and escalated ethanol consumption. Although negative affective states may drive escalated ethanol drinking, few reported studies examined the phenotypes together. However, there is significant overlap in the systems that were manipulated in relation to studying the phenotypes individually. These studies reveal common genetic influences on withdrawal-associated anxiety, convulsions, and escalated drinking that may contribute to relapse, setting the stage for the identification of novel medications to jointly target these effects.
Keywords: alcoholism; Animal; Animals; Anxiety; Consumption; Convulsion; Disease Models; Epilepsy; Ethanol withdrawal; gamma-Aminobutyric Acid; gene; Gene Targeting; Genetically Modified; Hyperkinesis; Knockout; Mood Disorders; Rodentia; Substance Withdrawal Syndrome; Transgenic

Genes and Alcohol Consumption: Studies with Mutant Mice - Mayfield, J.; Arends, M. A.; Harris, R. A.; Blednov, Y. A. (International Review of Neurobiology, 2016)
In this chapter, we review the effects of global null mutant and overexpressing transgenic mouse lines on voluntary self-administration of alcohol. We examine approximately 200 publications pertaining to the effects of 155 mouse genes on alcohol consumption in different drinking models. The targeted genes vary in function and include neurotransmitter, ion channel, neuroimmune, and neuropeptide signaling systems. The alcohol self-administration models include operant conditioning, two- and four-bottle choice continuous and intermittent access, drinking in the dark limited access, chronic intermittent ethanol, and scheduled high alcohol consumption tests. Comparisons of different drinking models using the same mutant mice are potentially the most informative, and we will highlight those examples. More mutants have been tested for continuous two-bottle choice consumption than any other test; of the 137 mouse genes examined using this model, 97 (72%) altered drinking in at least one sex. Overall, the effects of genetic manipulations on alcohol drinking often depend on the sex of the mice, alcohol concentration and time of access, genetic background, as well as the drinking test.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Choice Behavior; Conditioning; Continuous and intermittent two-bottle choice; Disease Models; Drinking in the dark; Ethanol; Global homozygous knockout; Knockin; Mice; Operant; Scheduled high alcohol consumption; Self Administration; Sex Characteristics; Transgenic; Transgenic overexpression; Voluntary self-administration

A Genetic Animal Model of Alcoholism for Screening Medications to Treat Addiction - Bell, R. L.; Hauser, S.; Rodd, Z. A.; Liang, T.; Sari, Y.; McClintick, J.; Rahman, S.; Engleman, E. A. (International Review of Neurobiology, 2016)
The purpose of this review is to present up-to-date pharmacological, genetic, and behavioral findings from the alcohol-preferring P rat and summarize similar past work. Behaviorally, the focus will be on how the P rat meets criteria put forth for a valid animal model of alcoholism with a highlight on its use as an animal model of polysubstance abuse, including alcohol, nicotine, and psychostimulants. Pharmacologically and genetically, the focus will be on the neurotransmitter and neuropeptide systems that have received the most attention: cholinergic, dopaminergic, GABAergic, glutamatergic, serotonergic, noradrenergic, corticotrophin releasing hormone, opioid, and neuropeptide Y. Herein, we sought to place the P rat's behavioral and neurochemical phenotypes, and to some extent its genotype, in the context of the clinical literature. After reviewing the findings thus far, this chapter discusses future directions for expanding the use of this genetic animal model of alcoholism to identify molecular targets for treating drug addiction in general.
Keywords: alcohol; alcoholism; Animal; animal models; Animals; CNS neurotransmitters; dependence; Disease Models; Drug addiction; Drug Evaluation; family history; Genomics; Humans; Pharmacogenetics; pharmacogenomics; Preclinical; predisposition; Proteomics; Selective breeding

Glutamatergic transmission in the central nucleus of the amygdala is selectively altered in Marchigian Sardinian alcohol-preferring rats: Alcohol and CRF effects - Herman, Melissa A.; Varodayan, Florence P.; Oleata, Christopher S.; Luu, George; Kirson, Dean; Heilig, Markus; Ciccocioppo, Roberto; Roberto, Marisa (Neuropharmacology, 2016)
The CRF system of the central nucleus of the amygdala (CeA) is important for the processing of anxiety, stress, and effects of acute and chronic ethanol. We previously reported that ethanol decreases evoked glutamate transmission in the CeA of Sprague Dawley rats and that ethanol dependence alters glutamate release in the CeA. Here, we examined the effects of ethanol, CRF and a CRF1 receptor antagonist on spontaneous and evoked glutamatergic transmission in CeA neurons from Wistar and Marchigian Sardinian Preferring (msP) rats, a rodent line genetically selected for excessive alcohol drinking and characterized by heightened activity of the CRF1 system. Basal spontaneous and evoked glutamate transmission in CeA neurons from msP rats was increased compared to Wistar rats. Ethanol had divergent effects, either increasing or decreasing spontaneous glutamate release in the CeA of Wistar rats. This bidirectional effect was retained in msP rats, but the magnitude of the ethanol-induced increase in glutamate release was significantly smaller. The inhibitory effect of ethanol on evoked glutamatergic transmission was similar in both strains. CRF also either increased or decreased spontaneous glutamate release in CeA neurons of Wistar rats, however, in msP rats CRF only increased glutamate release. The inhibitory effect of CRF on evoked glutamatergic transmission was also lost in neurons from msP rats. A CRF1 antagonist produced only minor effects on spontaneous glutamate transmission, which were consistent across strains, and no effects on evoked glutamate transmission. These results demonstrate that the genetically altered CRF system of msP rats results in alterations in spontaneous and stimulated glutamate signaling in the CeA that may contribute to both the anxiety and drinking behavioral phenotypes.
Keywords: alcohol; Alcohol Drinking; Amygdala; Animals; Central Amygdaloid Nucleus; Corticotropin-Releasing Hormone; CRF; CRF1 antagonist; Electrophysiology; Ethanol; Excitatory Postsynaptic Potentials; glutamate; Glutamic Acid; Neurons; Pyrimidines; Rats; Receptors; Wistar

GPR88 in A2AR Neurons Enhances Anxiety-Like Behaviors - Meirsman, Aura Carole; Robé, Anne; de Kerchove d'Exaerde, Alban; Kieffer, Brigitte Lina (eNeuro, 2016)
GPR88 is an orphan G-protein-coupled receptor highly expressed in striatal dopamine D1 (receptor) R- and D2R-expressing medium spiny neurons. This receptor is involved in activity and motor responses, and we previously showed that this receptor also regulates anxiety-like behaviors. To determine whether GPR88 in D2R-expressing neurons contributes to this emotional phenotype, we generated conditional Gpr88 knock-out mice using adenosine A2AR (A2AR)-Cre-driven recombination, and compared anxiety-related responses in both total and A2AR-Gpr88 KO mice. A2AR-Gpr88 KO mice showed a selective reduction of Gpr88 mRNA in D2R-expressing, but not D1R-expressing, neurons. These mutant mice showed increased locomotor activity and decreased anxiety-like behaviors in light/dark and elevated plus maze tests. These phenotypes were superimposable on those observed in total Gpr88 KO mice, demonstrating that the previously reported anxiogenic activity of GPR88 operates at the level of A2AR-expressing neurons. Further, A2AR-Gpr88 KO mice showed no change in novelty preference and novelty-suppressed feeding, while these responses were increased and decreased, respectively, in the total Gpr88 KO mice. Also, A2AR-Gpr88 KO mice showed intact fear conditioning, while the fear responses were decreased in total Gpr88 KO. We therefore also show for the first time that GPR88 activity regulates approach behaviors and conditional fear; however, these behaviors do not seem mediated by receptors in A2AR neurons. We conclude that Gpr88 expressed in A2AR neurons enhances ethological anxiety-like behaviors without affecting conflict anxiety and fear responses.
Keywords: amygdale; anxiety-like behavior; D2R-medium spiny neurons; G-protein-coupled receptors; striatum

Inhibition of IKKβ Reduces Ethanol Consumption in C57BL/6J Mice - Truitt, Jay M.; Blednov, Yuri A.; Benavidez, Jillian M.; Black, Mendy; Ponomareva, Olga; Law, Jade; Merriman, Morgan; Horani, Sami; Jameson, Kelly; Lasek, Amy W.; Harris, R. Adron; Mayfield, R. Dayne (eNeuro, 2016)
Proinflammatory pathways in neuronal and non-neuronal cells are implicated in the acute and chronic effects of alcohol exposure in animal models and humans. The nuclear factor-κB (NF-κB) family of DNA transcription factors plays important roles in inflammatory diseases. The kinase IKKβ mediates the phosphorylation and subsequent proteasomal degradation of cytosolic protein inhibitors of NF-κB, leading to activation of NF-κB. The role of IKKβ as a potential regulator of excessive alcohol drinking had not previously been investigated. Based on previous findings that the overactivation of innate immune/inflammatory signaling promotes ethanol consumption, we hypothesized that inhibiting IKKβ would limit/decrease drinking by preventing the activation of NF-κB. We studied the systemic effects of two pharmacological inhibitors of IKKβ, TPCA-1 and sulfasalazine, on ethanol intake using continuous- and limited-access, two-bottle choice drinking tests in C57BL/6J mice. In both tests, TPCA-1 and sulfasalazine reduced ethanol intake and preference without changing total fluid intake or sweet taste preference. A virus expressing Cre recombinase was injected into the nucleus accumbens and central amygdala to selectively knock down IKKβ in mice genetically engineered with a conditional Ikkb deletion (Ikkb(F/F) ). Although IKKβ was inhibited to some extent in astrocytes and microglia, neurons were a primary cellular target. Deletion of IKKβ in either brain region reduced ethanol intake and preference in the continuous access two-bottle choice test without altering the preference for sucrose. Pharmacological and genetic inhibition of IKKβ decreased voluntary ethanol consumption, providing initial support for IKKβ as a potential therapeutic target for alcohol abuse.
Keywords: alcohol; Astrocytes; Binge Drinking; central amygdala; Cre recombinase; DID; Microglia; Neurons; Nucleus Accumbens; sulfasalazine; TPCA-1

Localization of PPAR isotypes in the adult mouse and human brain - Warden, Anna; Truitt, Jay; Merriman, Morgan; Ponomareva, Olga; Jameson, Kelly; Ferguson, Laura B.; Mayfield, R. Dayne; Harris, R. Adron (Scientific Reports, 2016)
Peroxisome proliferator-activated receptors (PPARs) are nuclear hormone receptors that act as ligand-activated transcription factors. PPAR agonists have well-documented anti-inflammatory and neuroprotective roles in the central nervous system. Recent evidence suggests that PPAR agonists are attractive therapeutic agents for treating neurodegenerative diseases as well as addiction. However, the distribution of PPAR mRNA and protein in brain regions associated with these conditions (i.e. prefrontal cortex, nucleus accumbens, amygdala, ventral tegmental area) is not well defined. Moreover, the cell type specificity of PPARs in mouse and human brain tissue has yet to be investigated. We utilized quantitative PCR and double immunofluorescence microscopy to determine that both PPAR mRNA and protein are expressed ubiquitously throughout the adult mouse brain. We found that PPARs have unique cell type specificities that are consistent between species. PPARα was the only isotype to colocalize with all cell types in both adult mouse and adult human brain tissue. Overall, we observed a strong neuronal signature, which raises the possibility that PPAR agonists may be targeting neurons rather than glia to produce neuroprotection. Our results fill critical gaps in PPAR distribution and define novel cell type specificity profiles in the adult mouse and human brain.

Medications between psychiatric and addictive disorders - Lalanne, Laurence; Lutz, Pierre-Eric; Trojak, Benoit; Lang, Jean-Philippe; Kieffer, Brigitte L.; Bacon, Elisabeth (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2016)
INTRODUCTION: Many epidemiological studies have revealed a frequent co-occurrence of psychiatric and substance use disorders. The term used in the literature to refer to this co-occurrence is dual diagnosis. The high prevalence of dual diagnosis has led physicians to observe the effects of medication prescribed to treat psychiatric disorders on the co-occurring substance use disorder and vice versa. The concept of medications between psychiatric and addictive disorders stems from these clinical observations, alongside which, however, it has developed from the observation that both psychiatric and substance use disorders share common neurobiological pathways and trigger common cognitive disorders. This has led researchers to develop medications on the basis of neurobiological and cognitive rationales. MATERIAL AND METHOD: In our article, we review peculiar medications based on neurobiological and cognitive rationales and that have an impact in both psychiatric and addictive disorders. RESULTS: We highlight how interesting these new prescriptions are for clinical observation and for the treatment of patients suffering from dual diagnosis. CONCLUSION: We then go on to discuss the interest in them from the perspective of clinical practice and clinical research, in that the development of medications to treat dual diagnosis helps to further our knowledge of both psychiatric and substance use disorders.
Keywords: addiction; Animals; Clozapine; Cognition; Depression; diagnosis; Dual (Psychiatry); Dual diagnosis; Humans; Mirtazapine; Modafinil; Psychiatric disorders; Psychotropic Drugs; Schizophrenia; Substance-Related Disorders

Mice Lacking GPR88 Show Motor Deficit, Improved Spatial Learning, and Low Anxiety Reversed by Delta Opioid Antagonist - Meirsman, Aura C.; Le Merrer, Julie; Pellissier, Lucie P.; Diaz, Jorge; Clesse, Daniel; Kieffer, Brigitte L.; Becker, Jérôme A. J. (Biological Psychiatry, 2016)
BACKGROUND: GPR88 is an orphan G protein coupled receptor highly enriched in the striatum, and previous studies have focused on GPR88 function in striatal physiology. The receptor is also expressed in other brain areas, and here we examined whether GPR88 function extends beyond striatal-mediated responses. METHODS: We created Gpr88 knockout mice and examined both striatal and extrastriatal regions at molecular and cellular levels. We also tested striatum-, hippocampus-, and amygdala-dependent behaviors in Gpr88(-/-) mice using extensive behavioral testing. RESULTS: We found increased G protein coupling for delta opioid receptor (DOR) and mu opioid, but not other Gi/o coupled receptors, in the striatum of Gpr88 knockout mice. We also found modifications in gene transcription, dopamine and serotonin contents, and dendritic morphology inside and outside the striatum. Behavioral testing confirmed striatal deficits (hyperactivity, stereotypies, motor impairment in rotarod). In addition, mutant mice performed better in spatial tasks dependent on hippocampus (Y-maze, novel object recognition, dual solution cross-maze) and also showed markedly reduced levels of anxiety (elevated plus maze, marble burying, novelty suppressed feeding). Strikingly, chronic blockade of DOR using naltrindole partially improved motor coordination and normalized spatial navigation and anxiety of Gpr88(-/-) mice. CONCLUSIONS: We demonstrate that GPR88 is implicated in a large repertoire of behavioral responses that engage motor activity, spatial learning, and emotional processing. Our data also reveal functional antagonism between GPR88 and DOR activities in vivo. The therapeutic potential of GPR88 therefore extends to cognitive and anxiety disorders, possibly in interaction with other receptor systems.
Keywords: Ethological scoring of anxiety; Gene clustering; GPR88 agonist-induced GTPγS binding; Medium spiny neurons; Psychiatric disorders; Spatial learning

The neuroimmune transcriptome and alcohol dependence: potential for targeted therapies - Warden, Anna; Erickson, Emma; Robinson, Gizelle; Harris, R. Adron; Mayfield, R. Dayne (Pharmacogenomics, 2016)
Transcriptome profiling enables discovery of gene networks that are altered in alcoholic brains. This technique has revealed involvement of the brain's neuroimmune system in regulating alcohol abuse and dependence, and has provided potential therapeutic targets. In this review, we discuss Toll-like-receptor pathways, hypothesized to be key players in many stages of the alcohol addiction cycle. The growing appreciation of the neuroimmune system's involvement in alcoholism has also led to consideration of crucial roles for glial cells, including astrocytes and microglia, in the brain's response to alcohol abuse. We discuss current knowledge and hypotheses on the roles that specific neuroimmune cell types may play in addiction. Current strategies for repurposing US FDA-approved drugs for the treatment of alcohol use disorders are also discussed.
Keywords: alcohol; drug repurposing; Neuroimmune; Transcriptome

Neuropeptide Y response to alcohol is altered in nucleus accumbens of mice selectively bred for drinking to intoxication - Barkley-Levenson, Amanda M.; Ryabinin, Andrey E.; Crabbe, John C. (Behavioural Brain Research, 2016)
The High Drinking in the Dark (HDID) mice have been selectively bred for drinking to intoxicating blood alcohol levels and represent a genetic model of risk for binge-like drinking. Presently, little is known about the specific genetic factors that promote excessive intake in these mice. Previous studies have identified neuropeptide Y (NPY) as a potential target for modulating alcohol intake. NPY expression differs in some rodent lines that have been selected for high and low alcohol drinking phenotypes, as well as inbred mouse strains that differ in alcohol preference. Alcohol drinking and alcohol withdrawal also produce differential effects on NPY expression in the brain. Here, we assessed brain NPY protein levels in HDID mice of two replicates of selection and control heterogeneous stock (HS) mice at baseline (water drinking) and after binge-like alcohol drinking to determine whether selection is associated with differences in NPY expression and its sensitivity to alcohol. NPY levels did not differ between HDID and HS mice in any brain region in the water-drinking animals. HS mice showed a reduction in NPY levels in the nucleus accumbens (NAc) - especially in the shell - in ethanol-drinking animals vs. water-drinking controls. However, HDID mice showed a blunted NPY response to alcohol in the NAc core and shell compared to HS mice. These findings suggest that the NPY response to alcohol has been altered by selection for drinking to intoxication in a region-specific manner. Thus, the NPY system may represent a potential target for altering binge-like alcohol drinking in these mice.
Keywords: alcohol; Alcohol Drinking; Analysis of Variance; Animal; Animals; Behavioral genetics; Binge Drinking; Central Nervous System Depressants; Darkness; Disease Models; Drinking in the dark; Ethanol; Immunohistochemistry; Male; Mice; Neuropeptide Y; Nucleus Accumbens; Selective breeding; Time Factors

Npy deletion in an alcohol non-preferring rat model elicits differential effects on alcohol consumption and body weight - Qiu, Bin; Bell, Richard L.; Cao, Yong; Zhang, Lingling; Stewart, Robert B.; Graves, Tamara; Lumeng, Lawrence; Yong, Weidong; Liang, Tiebing (Journal of Genetics and Genomics = Yi Chuan Xue Bao, 2016)
Neuropeptide Y (NPY) is widely expressed in the central nervous system and influences many physiological processes. It is located within the rat quantitative trait locus (QTL) for alcohol preference on chromosome 4. Alcohol-nonpreferring (NP) rats consume very little alcohol, but have significantly higher NPY expression in the brain than alcohol-preferring (P) rats. We capitalized on this phenotypic difference by creating an Npy knockout (KO) rat using the inbred NP background to evaluate NPY effects on alcohol consumption. Zinc finger nuclease (ZNF) technology was applied, resulting in a 26-bp deletion in the Npy gene. RT-PCR, Western blotting and immunohistochemistry confirmed the absence of Npy mRNA and protein in KO rats. Alcohol consumption was increased in Npy(+/-) but not Npy(-/-) rats, while Npy(-/-) rats displayed significantly lower body weight when compared to Npy(+/+) rats. In whole brain tissue, expression levels of Npy-related and other alcohol-associated genes, Npy1r, Npy2r, Npy5r, Agrp, Mc3r, Mc4r, Crh and Crh1r, were significantly greater in Npy(-/-) rats, whereas Pomc and Crhr2 expressions were highest in Npy(+/-) rats. These findings suggest that the NPY-system works in close coordination with the melanocortin (MC) and corticotropin-releasing hormone (CRH) systems to modulate alcohol intake and body weight.
Keywords: Alcohol drinking behavior; BDNF; CRH and receptors; Knockout rat; Melanocortin and receptors; NPY and receptors

Peripheral Administration of Ethanol Results in a Correlated Increase in Dopamine and Serotonin Within the Posterior Ventral Tegmental Area - Deehan, Gerald A.; Knight, Christopher P.; Waeiss, R. Aaron; Engleman, Eric A.; Toalston, Jamie E.; McBride, William J.; Hauser, Sheketha R.; Rodd, Zachary A. (Alcohol and Alcoholism (Oxford, Oxfordshire), 2016)
AIMS: Two critical neurotransmitter systems regulating ethanol (EtOH) reward are serotonin (5-HT) and dopamine (DA). Within the posterior ventral tegmental area (pVTA), 5-HT receptors have been shown to regulate DA neuronal activity. Increased pVTA neuronal activity has been linked to drug reinforcement. The current experiment sought to determine the effect of EtOH on 5-HT and DA levels within the pVTA. METHODS: Wistar rats were implanted with cannula aimed at the pVTA. Neurochemical levels were determined using standard microdialysis procedures with concentric probes. Rats were randomly assigned to one of the five groups (n = 41; 7-9 per group) that were treated with 0-3.0 g/kg EtOH (intraperitoneally). RESULTS: Ethanol produced increased extracellular DA levels in the pVTA that resembled an inverted U-shape dose-response curve with peak levels (~200% of baseline) at the 2.25 g/kg dose. The increase in DA levels was observed for an extended period of time (~100 minutes). The effects of EtOH on extracellular 5-HT levels in the pVTA also resembled an inverted U-shape dose-response curve. However, increased 5-HT levels were only observed during the initial post-injection sample. The increases in extracellular DA and 5-HT levels were significantly correlated. CONCLUSION: The data indicate intraperitoneal EtOH administration stimulated the release of both 5-HT and DA within the pVTA, the levels of which were significantly correlated. Overall, the current findings suggest that the ability of EtOH to stimulate DA activity within the mesolimbic system may be modulated by increases in 5-HT release within the pVTA. SHORT SUMMARY: Two critical neurotransmitter systems regulating ethanol reward are serotonin and dopamine. The current experiment determined that intraperitoneal ethanol administration increased serotonin and dopamine levels within the pVTA (levels were significantly correlated). The current findings suggest the ability of EtOH to stimulate serotonin and dopamine activity within the mesolimbic system.
Keywords: Animals; dopamine; Dose-Response Relationship; Drug; Ethanol; Infusions; Male; Microdialysis; Parenteral; Rats; Reward; Serotonin; Ventral tegmental area; Wistar

PPAR Agonists: I. Role of Receptor Subunits in Alcohol Consumption in Male and Female Mice - Blednov, Yuri A.; Black, Mendy; Benavidez, Jillian M.; Stamatakis, Eleni E.; Harris, R. Adron (Alcoholism, Clinical and Experimental Research, 2016)
BACKGROUND: Several peroxisome proliferator-activated receptor (PPAR) agonists reduce voluntary alcohol consumption in rodent models, and evidence suggests that PPARα and γ subunits play an important role in this effect. To define the subunit dependence of this action, we tested selective PPARα and α/γ agonists and antagonists in addition to null mutant mice lacking PPARα. METHODS: The effects of fenofibrate (PPARα agonist) and tesaglitazar (PPARα/γ agonist) on continuous and intermittent 2-bottle choice drinking tests were examined in male and female wild-type mice and in male mice lacking PPARα. We compared the ability of MK886 (PPARα antagonist) and GW9662 (PPARγ antagonist) to inhibit the effects of fenofibrate and tesaglitazar in wild-type mice. The estrogen receptor antagonist, tamoxifen, can inhibit PPARγ-dependent transcription and was also studied in male and female mice. RESULTS: Fenofibrate and tesaglitazar reduced ethanol (EtOH) consumption and preference in wild-type mice, but these effects were not observed in mice lacking PPARα. MK886 inhibited the action of fenofibrate, but not tesaglitazer, while GW9662 did not inhibit either agonist. The PPAR agonists were more effective in male mice compared to females, and drinking in the continuous 2-bottle choice test was more sensitive to fenofibrate and tesaglitazar compared to drinking in the intermittent access test. Tamoxifen also reduced EtOH consumption in male mice and this action was inhibited by GW9662, but not MK886, suggesting that it acts by activation of PPARγ. CONCLUSIONS: Our study using selective PPAR agonists, antagonists, and null mutant mice indicates a key role for PPARα in mediating reduced EtOH consumption by fenofibrate and tesaglitazar.
Keywords: 129 Strain; Alcohol Drinking; Alkanesulfonates; Anilides; Animals; Dose-Response Relationship; Drug; Ethanol; Female; Fenofibrate; GW9662; Indoles; Knockout; Male; Mice; MK886; Phenylpropionates; PPAR alpha; PPAR gamma; PPAR α; Protein Subunits; Tesaglitazar

PPAR Agonists: II. Fenofibrate and Tesaglitazar Alter Behaviors Related to Voluntary Alcohol Consumption - Blednov, Yuri A.; Black, Mendy; Benavidez, Jillian M.; Stamatakis, Eleni E.; Harris, R. Adron (Alcoholism, Clinical and Experimental Research, 2016)
BACKGROUND: In the accompanying article, we showed that activation of peroxisome proliferator-activated receptor alpha (PPARα) signaling by fenofibrate and tesaglitazar decreases ethanol (EtOH) consumption in mice. In this study, we determined the role of these PPAR agonists in EtOH-related behaviors and other actions that may be important in regulating EtOH consumption. METHODS: The effects of fenofibrate (150 mg/kg) and tesaglitazar (1.5 mg/kg) were examined on the following responses in male and female C57BL/6J (B6) and B6 × 129S4 mice: preference for saccharin, EtOH-induced conditioned place preference (CPP), conditioned taste aversion (CTA), loss of righting reflex, and withdrawal, acoustic startle reflex, response to novelty, and EtOH clearance. Because the B6 inbred strain usually displays weak EtOH-induced CPP and weak EtOH-induced acute withdrawal, B6 × 129S4 mice were also studied. RESULTS: Fenofibrate and tesaglitazar decreased the novelty response and increased acute EtOH withdrawal severity, and fenofibrate increased EtOH-induced CTA. Two important factors for EtOH consumption (saccharin preference and EtOH-induced CPP) were not altered by fenofibrate or tesaglitazar. EtOH clearance was increased by both fenofibrate and tesaglitazar. Response to novelty, acute withdrawal, and EtOH clearance show sex differences and could contribute to the reduced EtOH consumption following fenofibrate administration. CONCLUSIONS: These studies indicate the complexity of EtOH-dependent and EtOH-independent behaviors that are altered by PPAR agonists and provide evidence for novel behavioral actions of these drugs that may contribute to PPAR-mediated effects on alcohol drinking.
Keywords: 129 Strain; Alcohol Drinking; Alkanesulfonates; Animals; Avoidance Learning; Classical; conditioned place preference; Conditioned taste aversion; Conditioning; Ethanol Withdrawal and Sedation; Female; Fenofibrate; Inbred C57BL; Locomotion; Male; Mice; Phenylpropionates; PPAR alpha; Reflex; Righting; Taste; Tesaglitazar

Prairie Voles as a Model to Screen Medications for the Treatment of Alcoholism and Addictions - Ryabinin, A. E.; Hostetler, C. M. (International Review of Neurobiology, 2016)
Most preclinical studies of medications to treat addictions are performed in mice and rats. These two rodent species belong to one phylogenetic subfamily, which narrows the likelihood of identifying potential mechanisms regulating addictions in other species, ie, humans. Expanding the genetic diversity of organisms modeling alcohol and drug abuse enhances our ability to screen for medications to treat addiction. Recently, research laboratories adapted the prairie vole model to study mechanisms of alcohol and drugs of abuse. This development not only expanded the diversity of genotypes used to screen medications, but also enhanced capabilities of such screens. Prairie voles belong to 3-5% of mammalian species exhibiting social monogamy. This unusual trait is reflected in their ability to form lasting long-term affiliations between adult individuals. The prairie vole animal model has high predictive validity for mechanisms regulating human social behaviors. In addition, these animals exhibit high alcohol intake and preference. In laboratory settings, prairie voles are used to model social influences on drug reward and alcohol consumption as well as effects of addictive substances on social bonding. As a result, this species can be adapted to screen medications whose effectiveness could be (a) resistant to social influences promoting excessive drug taking, (b) dependent on the presence of social support, and (c) medications affecting harmful social consequences of alcohol and drug abuse. This report reviews the literature on studies of alcohol and psychostimulants in prairie voles and discusses capabilities of this animal model as a screen for novel medications to treat alcoholism and addictions.
Keywords: alcoholism; Animal; animal model; Animals; Arvicolinae; Central Nervous System Stimulants; Disease Models; drug abuse; Drug Evaluation; Ethanol; Humans; Pair bonding; Prairie vole; Preclinical; Substance-Related Disorders

Progress With Nonhuman Animal Models of Addiction - Crabbe, John C. (Journal of Studies on Alcohol and Drugs, 2016)
Nonhuman animals have been major contributors to the science of the genetics of addiction. Given the explosion of interest in genetics, it is fair to ask, are we making reasonable progress toward our goals with animal models? I will argue that our goals are changing and that overall progress has been steady and seems likely to continue apace. Genetics tools have developed almost incredibly rapidly, enabling both more reductionist and more synthetic or integrative approaches. I believe that these approaches to making progress have been unbalanced in biomedical science, favoring reductionism, particularly in animal genetics. I argue that substantial, novel progress is also likely to come in the other direction, toward synthesis and abstraction. Another area in which future progress with genetic animal models seems poised to contribute more is the reconciliation of human and animal phenotypes, or consilience. The inherent power of the genetic animal models could be more profitably exploited. In the end, animal research has continued to provide novel insights about how genes influence individual differences in addiction risk and consequences. The rules of the genetics game are changing so fast that it is hard to remember how comparatively little we knew even a generation ago. Rather than worry about whether we have been wasting time and resources asking the questions we have been, we should look to the future and see if we can come up with some new ones. The valuable findings from the past will endure, and the sidetracks will be forgotten.

Protein Kinase C Epsilon Activity in the Nucleus Accumbens and Central Nucleus of the Amygdala Mediates Binge Alcohol Consumption - Cozzoli, Debra K.; Courson, Justin; Rostock, Charlotte; Campbell, Rianne R.; Wroten, Melissa G.; McGregor, Hadley; Caruana, Amanda L.; Miller, Bailey W.; Hu, Jia-Hua; Wu Zhang, Ping; Xiao, Bo; Worley, Paul F.; et al. (Biological Psychiatry, 2016)
BACKGROUND: Protein kinase C epsilon (PKCε) is emerging as a potential target for the development of pharmacotherapies to treat alcohol use disorders, yet little is known regarding how a history of a highly prevalent form of drinking, binge alcohol intake, influences enzyme priming or the functional relevance of kinase activity for excessive alcohol intake. METHODS: Immunoblotting was employed on tissue from subregions of the nucleus accumbens (NAc) and the amygdala to examine both idiopathic and binge drinking-induced changes in constitutive PKCε priming. The functional relevance of PKCε translocation for binge drinking and determination of potential upstream signaling pathways involved were investigated using neuropharmacologic approaches within the context of two distinct binge drinking procedures, drinking in the dark and scheduled high alcohol consumption. RESULTS: Binge alcohol drinking elevated p(Ser729)-PKCε levels in both the NAc and the central nucleus of the amygdala (CeA). Moreover, immunoblotting studies of selectively bred and transgenic mouse lines revealed a positive correlation between the propensity to binge drink alcohol and constitutive p(Ser729)-PKCε levels in the NAc and CeA. Finally, neuropharmacologic inhibition of PKCε translocation within both regions reduced binge alcohol consumption in a manner requiring intact group 1 metabotropic glutamate receptors, Homer2, phospholipase C, and/or phosphotidylinositide-3 kinase function. CONCLUSIONS: Taken together, these data indicate that PKCε signaling in both the NAc and CeA is a major contributor to binge alcohol drinking and to the genetic propensity to consume excessive amounts of alcohol.
Keywords: alcohol use disorders; Animals; Binge Drinking; Central Amygdaloid Nucleus; Drinking in the dark; Ethanol; glutamate; HDID-1 mice; Homer; Inbred C57BL; Metabotropic Glutamate; Mice; Nucleus Accumbens; Protein Kinase C-epsilon; Receptors; Scheduled high alcohol consumption; Signal Transduction; Transgenic

Recent Advances in Nicotinic Receptor Signaling in Alcohol Abuse and Alcoholism - Rahman, Shafiqur; Engleman, Eric A.; Bell, Richard L. (Progress in Molecular Biology and Translational Science, 2016)
Alcohol is the most commonly abused legal substance and alcoholism is a serious public health problem. It is a leading cause of preventable death in the world. The cellular and molecular mechanisms of alcohol reward and addiction are still not well understood. Emerging evidence indicates that unlike other drugs of abuse, such as nicotine, cocaine, or opioids, alcohol targets numerous channel proteins, receptor molecules, and signaling pathways in the brain. Previously, research has identified brain nicotinic acetylcholine receptors (nAChRs), a heterogeneous family of pentameric ligand-gated cation channels expressed in the mammalian brain, as critical molecular targets for alcohol abuse and dependence. Genetic variations encoding nAChR subunits have been shown to increase the vulnerability to develop alcohol dependence. Here, we review recent insights into the rewarding effects of alcohol, as they pertain to different nAChR subtypes, associated signaling molecules, and pathways that contribute to the molecular mechanisms of alcoholism and/or comorbid brain disorders. Understanding these cellular changes and molecular underpinnings may be useful for the advancement of brain nicotinic-cholinergic mechanisms, and will lead to a better translational and therapeutic outcome for alcoholism and/or comorbid conditions.
Keywords: Alcohol dependence; alcoholism; Animals; Drug addiction; drug targets; Genetically Modified; Humans; molecular mechanisms; Nicotine; Nicotinic; nicotinic receptor; Receptors; Signal Transduction; translational research

Reproducibility of Experiments with Laboratory Animals: What Should We Do Now? - Crabbe, John C. (Alcoholism, Clinical and Experimental Research, 2016)

The role of IL-17 signaling in regulation of the liver-brain axis and intestinal permeability in alcoholic liver disease. - Ma HY,; Xu J,; Liu X,; Zhu Y,; Gao B,; Karin M,; Tsukamoto H,; Jeste DV,; Grant I,; Roberts AJ,; Contet C; Geoffroy C,; et al. (Current Pathobiology Reports, 2016)
Alcoholic liver disease (ALD) progresses from a normal liver, to steatosis, steatohepatitis, fibrosis and hepatocellular carcinoma (HCC). Despite intensive studies, the pathogenesis of ALD is poorly understood, in part due to a lack of suitable animal models which mimic the stages of ALD progression. Furthermore, the role of IL-17 in ALD has not been evaluated. We and others have recently demonstrated that IL-17 signaling plays a critical role in development of liver fibrosis and cancer. Here we summarize the most recent evidence supporting the roleof IL-17 in ALD. As a result of a collaborative effort of Drs. Karin, Gao, Tsukamoto and Kisseleva, we developed several improved models of ALD in mice: 1) chronic-plus-binge model that mimics early stages of steatohepatitis, 2) intragastric ethanol feeding model that mimics alcoholic steatohepatitis and fibrosis, and 3) diethylnitrosamine (DEN)+alcohol model that mimics alcoholic liver cancer. These models might provide new insights into the mechanism of IL-17 signaling in ALD and help identify novel therapeutic targets.

Synaptic microRNAs Coordinately Regulate Synaptic mRNAs: Perturbation by Chronic Alcohol Consumption - Most, Dana; Leiter, Courtney; Blednov, Yuri A.; Harris, R. Adron; Mayfield, R. Dayne (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2016)
Local translation of mRNAs in the synapse has a major role in synaptic structure and function. Chronic alcohol use causes persistent changes in synaptic mRNA expression, possibly mediated by microRNAs localized in the synapse. We profiled the transcriptome of synaptoneurosomes (SN) obtained from the amygdala of mice that consumed 20% ethanol (alcohol) in a 30-day continuous two-bottle choice test to identify the microRNAs that target alcohol-induced mRNAs. SN are membrane vesicles containing pre- and post-synaptic compartments of neurons and astroglia and are a unique model for studying the synaptic transcriptome. We previously showed that chronic alcohol regulates mRNA expression in a coordinated manner. Here, we examine microRNAs and mRNAs from the same samples to define alcohol-responsive synaptic microRNAs and their predicted interactions with targeted mRNAs. The aim of the study was to identify the microRNA-mRNA synaptic interactions that are altered by alcohol. This was accomplished by comparing the effect of alcohol in SN and total homogenate preparations from the same samples. We used a combination of unbiased bioinformatic methods (differential expression, correlation, co-expression, microRNA-mRNA target prediction, co-targeting, and cell type-specific analyses) to identify key alcohol-sensitive microRNAs. Prediction analysis showed that a subset of alcohol-responsive microRNAs was predicted to target many alcohol-responsive mRNAs, providing a bidirectional analysis for identifying microRNA-mRNA interactions. We found microRNAs and mRNAs with overlapping patterns of expression that correlated with alcohol consumption. Cell type-specific analysis revealed that a significant number of alcohol-responsive mRNAs and microRNAs were unique to glutamate neurons and were predicted to target each other. Chronic alcohol consumption appears to perturb the coordinated microRNA regulation of mRNAs in SN, a mechanism that may explain the aberrations in synaptic plasticity affecting the alcoholic brain.
Keywords: Alcohol Drinking; Alcohol-Related Disorders; Animal; Animals; Brain; Central Nervous System Depressants; Choice Behavior; Disease Models; Ethanol; Female; Inbred C57BL; Messenger; Mice; Microarray Analysis; MicroRNAs; Real-Time Polymerase Chain Reaction; RNA; Synapses; Transcriptome

Transgenic mice with increased astrocyte expression of IL-6 show altered effects of acute ethanol on synaptic function - Hernandez, Ruben V.; Puro, Alana C.; Manos, Jessica C.; Huitron-Resendiz, Salvador; Reyes, Kenneth C.; Liu, Kevin; Vo, Khanh; Roberts, Amanda J.; Gruol, Donna L. (Neuropharmacology, 2016)
A growing body of evidence has revealed that resident cells of the central nervous system (CNS), and particularly the glial cells, comprise a neuroimmune system that serves a number of functions in the normal CNS and during adverse conditions. Cells of the neuroimmune system regulate CNS functions through the production of signaling factors, referred to as neuroimmune factors. Recent studies show that ethanol can activate cells of the neuroimmune system, resulting in the elevated production of neuroimmune factors, including the cytokine interleukin-6 (IL-6). Here we analyzed the consequences of this CNS action of ethanol using transgenic mice that express elevated levels of IL-6 through increased astrocyte expression (IL-6-tg) to model the increased IL-6 expression that occurs with ethanol use. Results show that increased IL-6 expression induces neuroadaptive changes that alter the effects of ethanol. In hippocampal slices from non-transgenic (non-tg) littermate control mice, synaptically evoked dendritic field excitatory postsynaptic potential (fEPSP) and somatic population spike (PS) at the Schaffer collateral to CA1 pyramidal neuron synapse were reduced by acute ethanol (20 or 60 mM). In contrast, acute ethanol enhanced the fEPSP and PS in hippocampal slices from IL-6 tg mice. Long-term synaptic plasticity of the fEPSP (i.e., LTP) showed the expected dose-dependent reduction by acute ethanol in non-tg hippocampal slices, whereas LTP in the IL-6 tg hippocampal slices was resistant to this depressive effect of acute ethanol. Consistent with altered effects of acute ethanol on synaptic function in the IL-6 tg mice, EEG recordings showed a higher level of CNS activity in the IL-6 tg mice than in the non-tg mice during the period of withdrawal from an acute high dose of ethanol. These results suggest a potential role for neuroadaptive effects of ethanol-induced astrocyte production of IL-6 as a mediator or modulator of the actions of ethanol on the CNS, including persistent changes in CNS function that contribute to cognitive dysfunction and the development of alcohol dependence.
Keywords: Animals; Astrocytes; Brain Waves; Cerebral Cortex; EEG; Electric Stimulation; Ethanol; Ethanol withdrawal hyperexcitability; Excitatory Postsynaptic Potentials; Gamma frequency; Glia; Hippocampus; Interleukin-6; Long-Term Potentiation; Mice; Neurofeedback; Neuroimmune; Neuronal Plasticity; Pyramidal Cells; Signal Transduction; STAT3; synaptic plasticity; Transgenic

Transgenic mice with increased astrocyte expression of IL-6 show altered effects of acute ethanol on synaptic function - Hernandez, Ruben V.; Puro, Alana C.; Manos, Jessica C.; Huitron-Resendiz, Salvador; Reyes, Kenneth C.; Liu, Kevin; Vo, Khanh; Roberts, Amanda J.; Gruol, Donna L. (Neuropharmacology, 2016)
A growing body of evidence has revealed that resident cells of the central nervous system (CNS), and particularly the glial cells, comprise a neuroimmune system that serves a number of functions in the normal CNS and during adverse conditions. Cells of the neuroimmune system regulate CNS functions through the production of signaling factors, referred to as neuroimmune factors. Recent studies show that ethanol can activate cells of the neuroimmune system, resulting in the elevated production of neuroimmune factors, including the cytokine interleukin-6 (IL-6). Here we analyzed the consequences of this CNS action of ethanol using transgenic mice that express elevated levels of IL-6 through increased astrocyte expression (IL-6-tg) to model the increased IL-6 expression that occurs with ethanol use. Results show that increased IL-6 expression induces neuroadaptive changes that alter the effects of ethanol. In hippocampal slices from non-transgenic (non-tg) littermate control mice, synaptically evoked dendritic field excitatory postsynaptic potential (fEPSP) and somatic population spike (PS) at the Schaffer collateral to CA1 pyramidal neuron synapse were reduced by acute ethanol (20 or 60 mM). In contrast, acute ethanol enhanced the fEPSP and PS in hippocampal slices from IL-6 tg mice. Long-term synaptic plasticity of the fEPSP (i.e., LTP) showed the expected dose-dependent reduction by acute ethanol in non-tg hippocampal slices, whereas LTP in the IL-6 tg hippocampal slices was resistant to this depressive effect of acute ethanol. Consistent with altered effects of acute ethanol on synaptic function in the IL-6 tg mice, EEG recordings showed a higher level of CNS activity in the IL-6 tg mice than in the non-tg mice during the period of withdrawal from an acute high dose of ethanol. These results suggest a potential role for neuroadaptive effects of ethanol-induced astrocyte production of IL-6 as a mediator or modulator of the actions of ethanol on the CNS, including persistent changes in CNS function that contribute to cognitive dysfunction and the development of alcohol dependence.
Keywords: Animals; Astrocytes; Brain Waves; Cerebral Cortex; EEG; Electric Stimulation; Ethanol; Ethanol withdrawal hyperexcitability; Excitatory Postsynaptic Potentials; Gamma frequency; Glia; Hippocampus; Interleukin-6; Long-Term Potentiation; Mice; Neurofeedback; Neuroimmune; Neuronal Plasticity; Pyramidal Cells; Signal Transduction; STAT3; synaptic plasticity; Transgenic

Transient CNS responses to repeated binge ethanol treatment - Zahr, Natalie M.; Rohlfing, Torsten; Mayer, Dirk; Luong, Richard; Sullivan, Edith V.; Pfefferbaum, Adolf (Addiction Biology, 2016)
The effects of ethanol (EtOH) on in vivo magnetic resonance (MR)-detectable brain measures across repeated exposures have not previously been reported. Of 28 rats weighing 340.66 ± 21.93 g at baseline, 15 were assigned to an EtOH group and 13 to a control group. Animals were exposed to five cycles of 4 days of intragastric (EtOH or dextrose) treatment and 10 days of recovery. Rats in both groups had structural MR imaging and whole-brain MR spectroscopy (MRS) scans at baseline, immediately following each binge period and after each recovery period (total = 11 scans per rat). Blood alcohol level at each of the five binge periods was ~300 mg/dl. Blood drawn at the end of the experiment did not show group differences for thiamine or its phosphate derivatives. Postmortem liver histopathology provided no evidence for hepatic steatosis, alcoholic hepatitis or alcoholic cirrhosis. Cerebrospinal fluid volumes of the lateral ventricles and cisterns showed enlargement with each binge EtOH exposure but recovery with each abstinence period. Similarly, changes in MRS metabolite levels were transient: levels of N-acetylaspartate and total creatine decreased, while those of choline-containing compounds and the combined resonance from glutamate and glutamine increased with each binge EtOH exposure cycle and then recovered during each abstinence period. Changes in response to EtOH were in expected directions based on previous single-binge EtOH exposure experiments, but the current MR findings do not provide support for accruing changes with repeated binge EtOH exposure.
Keywords: glutamate; MRI; MRS; repeated withdrawals; ventricles

Using In Vitro Electrophysiology to Screen Medications: Accumbal Plasticity as an Engram of Alcohol Dependence - Renteria, R.; Jeanes, Z. M.; Mangieri, R. A.; Maier, E. Y.; Kircher, D. M.; Buske, T. R.; Morrisett, R. A. (International Review of Neurobiology, 2016)
The nucleus accumbens (NAc) is a central component of the mesocorticolimbic reward system. Increasing evidence strongly implicates long-term synaptic neuroadaptations in glutamatergic excitatory activity of the NAc shell and/or core medium spiny neurons in response to chronic drug and alcohol exposure. Such neuroadaptations likely play a critical role in the development and expression of drug-seeking behaviors. We have observed unique cell-type-specific bidirectional changes in NAc synaptic plasticity (metaplasticity) following acute and chronic intermittent ethanol exposure. Other investigators have also previously observed similar metaplasticity in the NAc following exposure to psychostimulants, opiates, and amazingly, even following an anhedonia-inducing experience. Considering that the proteome of the postsynaptic density likely contains hundreds of biochemicals, proteins and other components and regulators, we believe that there is a large number of potential molecular sites through which accumbal metaplasticity may be involved in chronic alcohol abuse. Many of our companion laboratories are now engaged in identifying and screening medications targeting candidate genes and its products previously linked to maladaptive alcohol phenotypes. We hypothesize that if manipulation of such target genes and their products change NAc plasticity, then that observation constitutes an important validation step for the development of novel therapeutics to treat alcohol dependence.
Keywords: alcoholism; Animal; Animals; Central Nervous System Agents; Disease Models; Drug Evaluation; Genetically Modified; Humans; In Vitro Techniques; long-term depression; Medium spiny neuron; neuroadaptation; Neuronal Plasticity; Nucleus Accumbens; Preclinical; Synaptic

Adolescent Intermittent Alcohol Exposure: Dysregulation of Thrombospondins and Synapse Formation are Associated with Decreased Neuronal Density in the Adult Hippocampus - Risher, Mary-Louise; Sexton, Hannah G.; Risher, W. Christopher; Wilson, Wilkie A.; Fleming, Rebekah L.; Madison, Roger D.; Moore, Scott D.; Eroglu, Cagla; Swartzwelder, H. Scott (Alcoholism, Clinical and Experimental Research, 2015)
BACKGROUND: Adolescent intermittent alcohol exposure (AIE) has profound effects on neuronal function. We have previously shown that AIE causes aberrant hippocampal structure and function that persists into adulthood. However, the possible contributions of astrocytes and their signaling factors remain largely unexplored. We investigated the acute and enduring effects of AIE on astrocytic reactivity and signaling on synaptic expression in the hippocampus, including the impact of the thrombospondin (TSP) family of astrocyte-secreted synaptogenic factors and their neuronal receptor, alpha2delta-1 (α2δ-1). Our hypothesis is that some of the influences of AIE on neuronal function may be secondary to direct effects on astrocytes. METHODS: We conducted Western blot analysis on TSPs 1 to 4 and α2δ-1 from whole hippocampal lysates 24 hours after the 4th and 10th doses of AIE, then 24 days after the last dose (in adulthood). We used immunohistochemistry to assess astrocyte reactivity (i.e., morphology) and synaptogenesis (i.e., colocalization of pre- and postsynaptic puncta). RESULTS: Adolescent AIE reduced α2δ-1 expression, and colocalized pre- and postsynaptic puncta after the fourth ethanol (EtOH) dose. By the 10th dose, increased TSP2 levels were accompanied by an increase in colocalized pre- and postsynaptic puncta, while α2δ-1 returned to control levels. Twenty-four days after the last EtOH dose (i.e., adulthood), TSP2, TSP4, and α2δ-1 expression were all elevated. Astrocyte reactivity, indicated by increased astrocytic volume and area, was also observed at that time. CONCLUSIONS: Repeated EtOH exposure during adolescence results in long-term changes in specific astrocyte signaling proteins and their neuronal synaptogenic receptor. Continued signaling by these traditionally developmental factors in adulthood may represent a compensatory mechanism whereby astrocytes reopen the synaptogenic window and repair lost connectivity, and consequently contribute to the enduring maladaptive structural and functional abnormalities previously observed in the hippocampus after AIE.
Keywords: Adolescence; Age Factors; Animals; Astrocytes; Ethanol; Hippocampus; Male; Neurogenesis; Neurons; Rats; Sprague-Dawley; Synapses; Thrombospondin; Thrombospondins

Adolescent intermittent alcohol exposure: persistence of structural and functional hippocampal abnormalities into adulthood - Risher, Mary-Louise; Fleming, Rebekah L.; Risher, W. Christopher; Miller, K. M.; Klein, Rebecca C.; Wills, Tiffany; Acheson, Shawn K.; Moore, Scott D.; Wilson, Wilkie A.; Eroglu, Cagla; Swartzwelder, H. S. (Alcoholism, Clinical and Experimental Research, 2015)
BACKGROUND: Human adolescence is a crucial stage of neurological development during which ethanol (EtOH) consumption is often at its highest. Alcohol abuse during adolescence may render individuals at heightened risk for subsequent alcohol abuse disorders, cognitive dysfunction, or other neurological impairments by irreversibly altering long-term brain function. To test this possibility, we modeled adolescent alcohol abuse (i.e., intermittent EtOH exposure during adolescence [AIE]) in rats to determine whether adolescent exposure to alcohol leads to long-term structural and functional changes that are manifested in adult neuronal circuitry. METHODS: We specifically focused on hippocampal area CA1, a brain region associated with learning and memory. Using electrophysiological, immunohistochemical, and neuroanatomical approaches, we measured post-AIE changes in synaptic plasticity, dendritic spine morphology, and synaptic structure in adulthood. RESULTS: We found that AIE-pretreated adult rats manifest robust long-term potentiation, induced at stimulus intensities lower than those required in controls, suggesting a state of enhanced synaptic plasticity. Moreover, AIE resulted in an increased number of dendritic spines with characteristics typical of immaturity. Immunohistochemistry-based analysis of synaptic structures indicated a significant decrease in the number of co-localized pre- and postsynaptic puncta. This decrease is driven by an overall decrease in 2 postsynaptic density proteins, PSD-95 and SAP102. CONCLUSIONS: Taken together, these findings reveal that repeated alcohol exposure during adolescence results in enduring structural and functional abnormalities in the hippocampus. These synaptic changes in the hippocampal circuits may help to explain learning-related behavioral changes in adult animals preexposed to AIE.
Keywords: Adolescence; Aging; Animals; CA1 Region; Dendritic Spines; Ethanol; Hippocampal; Hippocampus; Intracellular Signaling Peptides and Proteins; Long-Term Potentiation; Male; Membrane Proteins; Neuropeptides; Rats; Synapses

Alcohol-preferring P rats emit spontaneous 22-28 kHz ultrasonic vocalizations that are altered by acute and chronic alcohol experience - Reno, James M.; Thakore, Neha; Gonzales, Rueben; Schallert, Timothy; Bell, Richard L.; Maddox, W. Todd; Duvauchelle, Christine L. (Alcoholism, Clinical and Experimental Research, 2015)
BACKGROUND: Emotional states are often thought to drive excessive alcohol intake and influence the development of alcohol use disorders. To gain insight into affective properties associated with excessive alcohol intake, we utilized ultrasonic vocalization (USV) detection and analyses to characterize the emotional phenotype of selectively bred alcohol-preferring (P) rats; an established animal model of excessive alcohol intake. USVs emitted by rodents have been convincingly associated with positive (50-55 kHz frequency-modulated [FM]) and negative (22-28 kHz) affective states. Therefore, we hypothesized that 50-55 and 22-28 kHz USV emission patterns in P rats would reveal a unique emotional phenotype sensitive to alcohol experience. METHODS: 50-55 kHz FM and 22-28 kHz USVs elicited from male P rats were assessed during access to water, 15 and 30% EtOH (v/v). Ethanol (EtOH; n = 12) or water only (Control; n = 4) across 8 weeks of daily drinking-in-the-dark (DID) sessions. RESULTS: Spontaneous 22-28 kHz USVs are emitted by alcohol-naïve P rats and are enhanced by alcohol experience. During DID sessions when alcohol was not available (e.g., "EtOH OFF" intervals), significantly more 22-28 kHz than 50-55 kHz USVs were elicited, while significantly more 50-55 kHz FM than 22-28 kHz USVs were emitted when alcohol was available (e.g., "EtOH ON" intervals). In addition, USV acoustic property analyses revealed chronic effects of alcohol experience on 22-28 kHz USV mean frequency, indicative of lasting alcohol-mediated alterations to neural substrates underlying emotional response. CONCLUSIONS: Our findings demonstrate that acute and chronic effects of alcohol exposure are reflected in changes in 22-28 and 50-55 kHz FM USV counts and acoustic patterns. These data support the notion that initiation and maintenance of alcohol intake in P rats may be due to a unique, alcohol-responsive emotional phenotype and further suggest that spontaneous 22-28 kHz USVs serve as behavioral markers for excessive drinking vulnerability.
Keywords: Animal; Animals; Drinking-in-the-dark; Emotional Status; Ethanol; Excessive Alcohol Intake; Inbred Strains; Male; Negative Affect; Rats; Self Administration; Vocalization; WAAVES

Amoxicillin and amoxicillin/clavulanate reduce ethanol intake and increase GLT-1 expression as well as AKT phosphorylation in mesocorticolimbic regions - Goodwani, Sunil; Rao, P. S. S.; Bell, Richard L.; Sari, Youssef (Brain Research, 2015)
Studies have shown that administration of the β-lactam antibiotic ceftriaxone (CEF) attenuates ethanol consumption and cocaine seeking behavior as well as prevents ethanol-induced downregulation of glutamate transporter 1 (GLT-1) expression in central reward brain regions. However, it is not known if these effects are compound-specific. Therefore, the present study examined the effects of two other β-lactam antibiotics, amoxicillin (AMOX) and amoxicillin/clavulanate (Augmentin, AUG), on ethanol drinking, as well as GLT-1 and phosphorylated-AKT (pAKT) levels in the nucleus accumbens (Acb) and medial prefrontal cortex (mPFC) of alcohol-preferring (P) rats. P rats were exposed to free-choice of ethanol (15% and 30%) for five weeks and were given five consecutive daily i.p. injections of saline vehicle, 100 mg/kg AMOX or 100mg/kg AUG. Both compounds significantly decreased ethanol intake and significantly increased GLT-1 expression in the Acb. AUG also increased GLT-1 expression in the mPFC. Results for changes in pAKT levels matched those for GLT-1, indicating that β-lactam antibiotic-induced reductions in ethanol intake are negatively associated with increases in GLT-1 and pAKT levels within two critical brains regions mediating drug reward and reinforcement. These findings add to a growing literature that pharmacological increases in GLT-1 expression are associated with decreases in ethanol intake and suggest that one mechanism mediating this effect may be increased phosphorylation of AKT. Thus, GLT-1 and pAKT may serve as molecular targets for the treatment of alcohol and drug abuse/dependence.
Keywords: AKT; Alcohol Deterrents; Alcohol Drinking; Amoxicillin; Animal; Animals; Anti-Bacterial Agents; Augmentin; Ceftriaxone; Central Nervous System Depressants; Choice Behavior; Clavulanate; Dietary Sucrose; Disease Models; Ethanol; Excitatory Amino Acid Transporter 2; GLT-1; Male; Nucleus Accumbens; Phosphorylation; Prefrontal Cortex; Proto-Oncogene Proteins c-akt; Random Allocation; Rats; Water

Applying the new genomics to alcohol dependence - Farris, Sean P.; Pietrzykowski, Andrzej Z.; Miles, Michael F.; O'Brien, Megan A.; Sanna, Pietro P.; Zakhari, Samir; Mayfield, R. Dayne; Harris, R. Adron (Alcohol (Fayetteville, N.Y.), 2015)
This review summarizes the proceedings of a symposium presented at the "Alcoholism and Stress: A Framework for Future Treatment Strategies" conference held in Volterra, Italy on May 6-9, 2014. The overall goal of the symposium titled "Applying the New Genomics to Alcohol Dependence", chaired by Dr. Adron Harris, was to highlight recent genomic discoveries and applications for profiling alcohol use disorder (AUD). Dr. Sean Farris discussed the gene expression networks related to lifetime consumption of alcohol within human prefrontal cortex. Dr. Andrzej Pietrzykowski presented the effects of alcohol on microRNAs in humans and animal models. Alcohol-induced alterations in the synaptic transcriptome were discussed by Dr. Michael Miles. Dr. Pietro Sanna examined methods to probe the gene regulatory networks that drive excessive alcohol drinking, and Dr. Samir Zakhari served as a panel discussant and summarized the proceedings. Collectively, the presentations emphasized the power of integrating multiple levels of genetics and transcriptomics with convergent biological processes and phenotypic behaviors to determine causal factors of AUD. The combined use of diverse data types demonstrates how unique approaches and applications can help categorize genetic complexities into relevant biological networks using a systems-level model of disease.
Keywords: alcoholism; Animals; Epigenesis; Epigenetics; Gene expression networks; Gene Expression Profiling; Gene Expression Regulation; Gene Regulatory Networks; Genetic; Genomics; Humans; MicroRNAs; RNA; RNA-seq; Sequence Analysis; Synaptic transcriptome; Systems Biology; Transcriptome

The bed nucleus of the stria terminalis regulates ethanol-seeking behavior in mice - Pina, Melanie M.; Young, Emily A.; Ryabinin, Andrey E.; Cunningham, Christopher L. (Neuropharmacology, 2015)
Drug-associated stimuli are considered important factors in relapse to drug use. In the absence of drug, these cues can trigger drug craving and drive subsequent drug seeking. One structure that has been implicated in this process is the bed nucleus of the stria terminalis (BNST), a chief component of the extended amygdala. Previous studies have established a role for the BNST in cue-induced cocaine seeking. However, it is unclear if the BNST underlies cue-induced seeking of other abused drugs such as ethanol. In the present set of experiments, BNST involvement in ethanol-seeking behavior was assessed in male DBA/2J mice using the conditioned place preference procedure (CPP). The BNST was inhibited during CPP expression using electrolytic lesions (Experiment 1), co-infusion of GABAA and GABAB receptor agonists muscimol and baclofen (M+B; Experiment 2), and activation of inhibitory designer receptors exclusively activated by designer drugs (hM4Di-DREADD) with clozapine-N-oxide (CNO; Experiment 3). The magnitude of ethanol CPP was reduced significantly by each of these techniques. Notably, infusion of M+B (Exp. 2) abolished CPP altogether. Follow-up studies to Exp. 3 showed that ethanol cue-induced c-Fos immunoreactivity in the BNST was reduced by hM4Di activation (Experiment 4) and in the absence of hM4Di, CNO did not affect ethanol CPP (Experiment 5). Combined, these findings demonstrate that the BNST is involved in the modulation of cue-induced ethanol-seeking behavior.
Keywords: alcohol; Alcohol-Related Disorders; Amygdala; Animal; Animals; Bed nucleus of the stria terminalis (BNST); c-Fos; Central Nervous System Depressants; Chemogenetic; Choice Behavior; Clozapine-N-oxide (CNO); Conditioning (Psychology); CPP; Cues; DBA/2J; dBNST; Disease Models; DREADD; Drug-Seeking Behavior; Ethanol; hM4Di; Inactivation; Inbred DBA; Lesion; Male; Mice; Microinfusion; Microinjection; Motor Activity; Place preference; Random Allocation; RASSL; Septal Nuclei; Spatial Behavior; vBNST

Behavioral and Genetic Evidence for GIRK Channels in the CNS: Role in Physiology, Pathophysiology, and Drug Addiction - Mayfield, Jody; Blednov, Yuri A.; Harris, R. Adron (International Review of Neurobiology, 2015)
G protein-coupled inwardly rectifying potassium (GIRK) channels are widely expressed throughout the brain and mediate the inhibitory effects of many neurotransmitters. As a result, these channels are important for normal CNS function and have also been implicated in Down syndrome, Parkinson's disease, psychiatric disorders, epilepsy, and drug addiction. Knockout mouse models have provided extensive insight into the significance of GIRK channels under these conditions. This review examines the behavioral and genetic evidence from animal models and genetic association studies in humans linking GIRK channels with CNS disorders. We further explore the possibility that subunit-selective modulators and other advanced research tools will be instrumental in establishing the role of individual GIRK subunits in drug addiction and other relevant CNS diseases and in potentially advancing treatment options for these disorders.
Keywords: Animals; Anxiety; Brain; Cocaine; Depression; Down syndrome; Epilepsy; Ethanol; G Protein-Coupled Inwardly-Rectifying Potassium Channels; Genetic Association Studies; Humans; Knockout; Knockout mice; Mice; Opioids; Parkinson's disease; Schizophrenia; Sedative–hypnotics; Substance-Related Disorders

BK Channel β1 Subunit Contributes to Behavioral Adaptations Elicited by Chronic Intermittent Ethanol Exposure - Kreifeldt, Max; Cates-Gatto, Chelsea; Roberts, Amanda J.; Contet, Candice (Alcoholism, Clinical and Experimental Research, 2015)
BACKGROUND: Large conductance, calcium- and voltage-activated potassium (BK) channels regulate neuronal excitability and neurotransmission. They can be directly activated by ethanol (EtOH) and they may be implicated in EtOH dependence. In this study, we sought to determine the influence of the auxiliary β1 and β4 subunits on EtOH metabolism, acute sensitivity to EtOH intoxication, acute functional tolerance, chronic tolerance, and handling-induced convulsions during withdrawal. METHODS: Motor coordination, righting reflex, and body temperature were evaluated in BK β1 and β4 knockout, heterozygous, and wild-type mice following acute EtOH administration. Chronic tolerance and physical dependence were induced by chronic intermittent inhalation of EtOH vapor. RESULTS: Constitutive deficiency in BK β1 or β4 subunits did not alter the clearance rate of EtOH, acute sensitivity to EtOH-induced ataxia, sedation, and hypothermia, nor acute functional tolerance to ataxia. BK β1 deletion reduced chronic tolerance to sedation and abolished chronic tolerance to hypothermia, while BK β4 deletion did not affect these adaptations to chronic EtOH exposure. Finally, the absence of BK β1 accelerated the appearance, while the absence of BK β4 delayed the resolution, of the hyperexcitable state associated with EtOH withdrawal. CONCLUSIONS: Altogether, the present findings reveal the critical role of BK β1 in behavioral adaptations to prolonged, repeated EtOH intoxication.
Keywords: Adaptation; alcohol; Animals; dependence; Ethanol; Hypnotics and Sedatives; Hypothermia; Inbred C57BL; Intoxication; Knockout; Knockout mice; Large-Conductance Calcium-Activated Potassium Channels; Mice; Physiological; Protein Subunits; vapor chambers

Brain pathways to recovery from alcohol dependence - Cui, Changhai; Noronha, Antonio; Warren, Kenneth R.; Koob, George F.; Sinha, Rajita; Thakkar, Mahesh; Matochik, John; Crews, Fulton T.; Chandler, L. Judson; Pfefferbaum, Adolf; Becker, Howard C.; Lovinger, David; et al. (Alcohol (Fayetteville, N.Y.), 2015)
This article highlights the research presentations at the satellite symposium on "Brain Pathways to Recovery from Alcohol Dependence" held at the 2013 Society for Neuroscience Annual Meeting. The purpose of this symposium was to provide an up to date overview of research efforts focusing on understanding brain mechanisms that contribute to recovery from alcohol dependence. A panel of scientists from the alcohol and addiction research field presented their insights and perspectives on brain mechanisms that may underlie both recovery and lack of recovery from alcohol dependence. The four sessions of the symposium encompassed multilevel studies exploring mechanisms underlying relapse and craving associated with sustained alcohol abstinence, cognitive function deficit and recovery, and translational studies on preventing relapse and promoting recovery. Gaps in our knowledge and research opportunities were also discussed.
Keywords: Abstinence; Addictive; Alcohol dependence; alcoholism; Behavior; Brain; Cognition; Humans; Neural Pathways; neuroadaptation; Neurocircuitry; Neuronal Plasticity; recovery; Substance Withdrawal Syndrome; withdrawal

The central amygdala as an integrative hub for anxiety and alcohol use disorders - Gilpin, Nicholas W.; Herman, Melissa A.; Roberto, Marisa (Biological Psychiatry, 2015)
The central amygdala (CeA) plays a central role in physiologic and behavioral responses to fearful stimuli, stressful stimuli, and drug-related stimuli. The CeA receives dense inputs from cortical regions, is the major output region of the amygdala, is primarily GABAergic (inhibitory), and expresses high levels of prostress and antistress peptides. The CeA is also a constituent region of a conceptual macrostructure called the extended amygdala that is recruited during the transition to alcohol dependence. We discuss neurotransmission in the CeA as a potential integrative hub between anxiety disorders and alcohol use disorder, which are commonly co-occurring in humans. Imaging studies in humans and multidisciplinary work in animals collectively suggest that CeA structure and function are altered in individuals with anxiety disorders and alcohol use disorder, the end result of which may be disinhibition of downstream "effector" regions that regulate anxiety-related and alcohol-related behaviors.
Keywords: alcoholism; Animals; Anxiety; Anxiety disorder; Central Amygdaloid Nucleus; Corticotropin-Releasing Hormone; CRF; Ethanol; Extended amygdala; GABA; Humans; Neurons; Neuropeptide Y; NPY; Posttraumatic stress disorder; Psychological; Signal Transduction; Stress

Chronic ethanol exposure produces time- and brain region-dependent changes in gene coexpression networks - Osterndorff-Kahanek, Elizabeth A.; Becker, Howard C.; Lopez, Marcelo F.; Farris, Sean P.; Tiwari, Gayatri R.; Nunez, Yury O.; Harris, R. Adron; Mayfield, R. Dayne (PloS One, 2015)
Repeated ethanol exposure and withdrawal in mice increases voluntary drinking and represents an animal model of physical dependence. We examined time- and brain region-dependent changes in gene coexpression networks in amygdala (AMY), nucleus accumbens (NAC), prefrontal cortex (PFC), and liver after four weekly cycles of chronic intermittent ethanol (CIE) vapor exposure in C57BL/6J mice. Microarrays were used to compare gene expression profiles at 0-, 8-, and 120-hours following the last ethanol exposure. Each brain region exhibited a large number of differentially expressed genes (2,000-3,000) at the 0- and 8-hour time points, but fewer changes were detected at the 120-hour time point (400-600). Within each region, there was little gene overlap across time (~20%). All brain regions were significantly enriched with differentially expressed immune-related genes at the 8-hour time point. Weighted gene correlation network analysis identified modules that were highly enriched with differentially expressed genes at the 0- and 8-hour time points with virtually no enrichment at 120 hours. Modules enriched for both ethanol-responsive and cell-specific genes were identified in each brain region. These results indicate that chronic alcohol exposure causes global 'rewiring' of coexpression systems involving glial and immune signaling as well as neuronal genes.
Keywords: Animals; Brain; Ethanol; Gene Regulatory Networks; Genetic; Inbred C57BL; Liver; Male; Mice; Organ Specificity; Time Factors; Transcription; Transcriptome

Commonalities and Distinctions Among Mechanisms of Addiction to Alcohol and Other Drugs - Ozburn, Angela R.; Janowsky, Aaron J.; Crabbe, John C. (Alcoholism, Clinical and Experimental Research, 2015)
BACKGROUND: Alcohol abuse is comorbid with abuse of many other drugs, some with similar pharmacology and others quite different. This leads to the hypothesis of an underlying, unitary dysfunctional neurobiological basis for substance abuse risk and consequences. METHODS: In this review, we discuss commonalities and distinctions of addiction to alcohol and other drugs. We focus on recent advances in preclinical studies using rodent models of drug self-administration. RESULTS: While there are specific behavioral and molecular manifestations common to alcohol, psychostimulant, opioid, and nicotine dependence, attempts to propose a unifying theory of the addictions inevitably face details where distinctions are found among classes of drugs. CONCLUSIONS: For alcohol, versus other drugs of abuse, we discuss and compare advances in: (i) neurocircuitry important for the different stages of drug dependence; (ii) transcriptomics and genetical genomics; and (iii) enduring effects, noting in particular the contributions of behavioral genetics and animal models.
Keywords: addiction; Addictive; alcohol; alcoholism; Animal; animal models; Animals; Behavior; Cocaine; Disease Models; Drugs of abuse; Genomics; Humans; Neural Pathways; Self Administration; Substance-Related Disorders; Transcriptome

Cosplicing network analysis of mammalian brain RNA-Seq data utilizing WGCNA and Mantel correlations - Iancu, Ovidiu D.; Colville, Alexandre; Oberbeck, Denesa; Darakjian, Priscila; McWeeney, Shannon K.; Hitzemann, Robert (Frontiers in Genetics, 2015)
Across species and tissues and especially in the mammalian brain, production of gene isoforms is widespread. While gene expression coordination has been previously described as a scale-free coexpression network, the properties of transcriptome-wide isoform production coordination have been less studied. Here we evaluate the system-level properties of cosplicing in mouse, macaque, and human brain gene expression data using a novel network inference procedure. Genes are represented as vectors/lists of exon counts and distance measures sensitive to exon inclusion rates quantifies differences across samples. For all gene pairs, distance matrices are correlated across samples, resulting in cosplicing or cotranscriptional network matrices. We show that networks including cosplicing information are scale-free and distinct from coexpression. In the networks capturing cosplicing we find a set of novel hubs with unique characteristics distinguishing them from coexpression hubs: heavy representation in neurobiological functional pathways, strong overlap with markers of neurons and neuroglia, long coding lengths, and high number of both exons and annotated transcripts. Further, the cosplicing hubs are enriched in genes associated with autism spectrum disorders. Cosplicing hub homologs across eukaryotes show dramatically increasing intronic lengths but stable coding region lengths. Shared transcription factor binding sites increase coexpression but not cosplicing; the reverse is true for splicing-factor binding sites. Genes with protein-protein interactions have strong coexpression and cosplicing. Additional factors affecting the networks include shared microRNA binding sites, spatial colocalization within the striatum, and sharing a chromosomal folding domain. Cosplicing network patterns remain relatively stable across species.
Keywords: Alternative Splicing; brain transcriptome; gene coexpression; gene cosplicing; scale-free gene networks

Cross-sectional versus longitudinal estimates of age-related changes in the adult brain: overlaps and discrepancies - Pfefferbaum, Adolf; Sullivan, Edith V. (Neurobiology of Aging, 2015)
The healthy adult brain undergoes tissue volume decline with age, but contradictory findings abound regarding rate of change. To identify a source of this discrepancy, we present contrasting statistical approaches to estimate hippocampal volume change with age based on 200 longitudinally-acquired magnetic resonance imaging in 70 healthy adults, age 20-70 years, who had 2-5 magnetic resonance imaging collected over 6 months to 8 years. Linear mixed-effects modeling using volume trajectories over age for each subject revealed significantly negative slopes with aging after a linear decline with a suggestion of acceleration in older individuals. By contrast, general linear modeling using either the first observation only of each subject or all observations treated independently (thereby disregarding trajectories) indicated no significant correlation between volume and age. Entering a quadratic term into the linear model yielded a biologically plausible function that was not supported by longitudinal analysis. The results underscore the importance of analyses that incorporate the trajectory of individuals in the study of brain aging.
Keywords: Adult; Age Factors; Aged; Aging; Aging MRI; Atlas-based parcellation; Brain; Computer-Assisted; Cross-sectional; Cross-Sectional Studies; Female; Hippocampus; Humans; Image Processing; Linear mixed-effects model; Linear Models; Longitudinal; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Young Adult

Delta opioid receptors expressed in forebrain GABAergic neurons are responsible for SNC80-induced seizures - Chu Sin Chung, Paul; Boehrer, Annie; Stephan, Aline; Matifas, Audrey; Scherrer, Grégory; Darcq, Emmanuel; Befort, Katia; Kieffer, Brigitte L. (Behavioural Brain Research, 2015)
The delta opioid receptor (DOR) has raised much interest for the development of new therapeutic drugs, particularly to treat patients suffering from mood disorders and chronic pain. Unfortunately, the prototypal DOR agonist SNC80 induces mild epileptic seizures in rodents. Although recently developed agonists do not seem to show convulsant properties, mechanisms and neuronal circuits that support DOR-mediated epileptic seizures remain to be clarified. DORs are expressed throughout the nervous system. In this study we tested the hypothesis that SNC80-evoked seizures stem from DOR activity at the level of forebrain GABAergic transmission, whose inhibition is known to facilitate the development of epileptic seizures. We generated a conditional DOR knockout mouse line, targeting the receptor gene specifically in GABAergic neurons of the forebrain (Dlx-DOR). We measured effects of SNC80 (4.5, 9, 13.5 and 32 mg/kg), ARM390 (10, 30 and 60 mg/kg) or ADL5859 (30, 100 and 300 mg/kg) administration on electroencephalograms (EEGs) recorded in Dlx-DOR mice and their control littermates (Ctrl mice). SNC80 produced dose-dependent seizure events in Ctrl mice, but these effects were not detected in Dlx-DOR mice. As expected, ARM390 and ADL5859 did not trigger any detectable change in mice from both genotypes. These results demonstrate for the first time that SNC80-induced DOR activation induces epileptic seizures via direct inhibition of GABAergic forebrain neurons, and supports the notion of differential activities between first and second-generation DOR agonists.
Keywords: Analgesics; Animal; Animals; Benzamides; Benzopyrans; Biased agonism; Conditional knockout; delta; Delta agonist; Delta opioid receptor; Disease Models; Dose-Response Relationship; Drug; Electroencephalography; Epileptic seizure; GABAergic Neurons; Gene Expression Regulation; In vivo; Knockout; Mice; Opioid; Piperazines; Prosencephalon; Reaction Time; Receptors; Seizures

Differential effects of ghrelin antagonists on alcohol drinking and reinforcement in mouse and rat models of alcohol dependence - Gomez, Juan L.; Cunningham, Christopher L.; Finn, Deborah A.; Young, Emily A.; Helpenstell, Lily K.; Schuette, Lindsey M.; Fidler, Tara L.; Kosten, Therese A.; Ryabinin, Andrey E. (Neuropharmacology, 2015)
An effort has been mounted to understand the mechanisms of alcohol dependence in a way that may allow for greater efficacy in treatment. It has long been suggested that drugs of abuse seize fundamental reward pathways and disrupt homeostasis to produce compulsive drug seeking behaviors. Ghrelin, an endogenous hormone that affects hunger state and release of growth hormone, has been shown to increase alcohol intake following administration, while antagonists decrease intake. Using rodent models of dependence, the current study examined the effects of two ghrelin receptor antagonists, [DLys3]-GHRP-6 (DLys) and JMV2959, on dependence-induced alcohol self-administration. In two experiments adult male C57BL/6J mice and Wistar rats were made dependent via intermittent ethanol vapor exposure. In another experiment, adult male C57BL/6J mice were made dependent using the intragastric alcohol consumption (IGAC) procedure. Ghrelin receptor antagonists were given prior to voluntary ethanol drinking. Ghrelin antagonists reduced ethanol intake, preference, and operant self-administration of ethanol and sucrose across these models, but did not decrease food consumption in mice. In experiments 1 and 2, voluntary drinking was reduced by ghrelin receptor antagonists, however this reduction did not persist across days. Despite the transient effects of ghrelin antagonists, the drugs had renewed effectiveness following a break in administration as seen in experiment 1. The results show the ghrelin system as a potential target for studies of alcohol abuse. Further research is needed to determine the central mechanisms of these drugs and their influence on addiction in order to design effective pharmacotherapies.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Central Nervous System Agents; Conditioning; Disease Models; Dose-Response Relationship; Drug; Ethanol; Ethanol vapor; Food Preferences; Ghrelin; Glycine; Inbred C57BL; Intragastric infusions; Male; Mice; Operant; Random Allocation; Rats; Receptors; Reinforcement (Psychology); Self Administration; self-administration; Triazoles; Two-bottle choice; Wistar

Distinct ethanol drinking microstructures in two replicate lines of mice selected for drinking to intoxication - Barkley-Levenson, A. M.; Crabbe, J. C. (Genes, Brain, and Behavior, 2015)
The High Drinking in the Dark (HDID) mice have been selectively bred for reaching high blood ethanol concentrations (BECs) following the limited access Drinking in the Dark (DID) test. We have shown previously that mice from the first HDID replicate line (HDID-1) drink in larger, but not longer, ethanol drinking bouts than the low-drinking HS/Npt control mice when consuming modest amounts in the DID test. Here, we assessed drinking microstructure in HDID-1 mice during binge-like levels of ethanol intake using a lickometer system. Mice from both HDID replicates (HDID-1 and -2) and HS mice were also given three DID tests (single-bottle ethanol, two-bottle choice and single-bottle saccharin) using a continuously recording BioDAQ system to determine whether there are selection-dependent changes in drinking microstructure. Larger ethanol bout size in the HDID-1 mice than the HS mice was found to be due to a larger lick volume in these mice. HDID-1 and HDID-2 mice were also seen to have different drinking microstructures that both resulted in high intake and high BECs. The HDID-1 mice drank in larger ethanol bouts than HS, whereas HDID-2 mice drank in more frequent bouts. This pattern was also seen in two-bottle choice DID. The HDID-2 mice had a high bout frequency for all fluid types tested, whereas the large bout size phenotype of the HDID-1 mice was specific to alcohol. These findings suggest that selection for drinking to intoxication has resulted in two distinct drinking microstructures, both of which lead to high BECs and high ethanol intake.
Keywords: alcohol; Alcoholic Intoxication; Animal; Animals; Behavior; Binge Drinking; BioDAQ; Drinking in the dark; Female; Genetic; Inbred Strains; lickometer; Male; Mice; microstructure; replicate lines; Saccharin; Selection; Selective breeding; Two-bottle choice

Dynamic responses of selective brain white matter fiber tracts to binge alcohol and recovery in the rat - Pfefferbaum, Adolf; Zahr, Natalie M.; Mayer, Dirk; Rohlfing, Torsten; Sullivan, Edith V. (PloS One, 2015)
To determine the dynamics of white matter vulnerability to excessive alcohol consumption, diffusion tensor imaging (DTI) was used in an animal model of alcohol exposure. Quantitative, in vivo fiber tracking results are presented from rats with DTI conducted at 3 time points: baseline; after 4 days of intragastric alcohol to blood alcohol levels of ~250 mg/dL; and after one week of recovery. Binge alcohol followed by a week of sobriety resulted in rapidly reversible decreases in fractional anisotropy (FA), a measure of the coherence of fiber tracts, in callosal genu and fimbria-fornix but not splenium; and increases in mean diffusivity (MD), an index of freely diffusing water in tissue, selective to the fimbria-fornix. These effects were confirmed with tract-based spatial statistics (TBSS). The directionality of changes in DTI metrics reproduce those observed in human alcoholism. That a single exposure to binge alcohol can cause substantial transient changes detectable in DTI metrics demonstrates the potential for rapid neuroplasticity.
Keywords: Animals; Anisotropy; Binge Drinking; Computer-Assisted; Diffusion Tensor Imaging; Ethanol; Image Processing; Male; Rats; Time Factors; White Matter; Wistar

Effects of ampicillin, cefazolin and cefoperazone treatments on GLT-1 expressions in the mesocorticolimbic system and ethanol intake in alcohol-preferring rats - Rao, P. S. S.; Goodwani, S.; Bell, R. L.; Wei, Y.; Boddu, S. H. S.; Sari, Y. (Neuroscience, 2015)
Chronic ethanol consumption is known to downregulate expression of the major glutamate transporter 1 (GLT-1), which increases extracellular glutamate concentrations in subregions of the mesocorticolimbic reward pathway. While β-lactam antibiotics were initially identified as potent upregulators of GLT-1 expression, only ceftriaxone has been extensively studied in various drug addiction models. Therefore, in this study, adult male alcohol-preferring (P) rats exposed chronically to ethanol were treated with other β-lactam antibiotics, ampicillin, cefazolin or cefoperazone (100mg/kg) once daily for five consecutive days to assess their effects on ethanol consumption. The results demonstrated that each compound significantly reduced ethanol intake compared to the saline-treated control group. Importantly, each compound significantly upregulated both GLT-1 and pAKT expressions in the nucleus accumbens and prefrontal cortex compared to saline-treated control group. In addition, only cefoperazone significantly inhibited hepatic aldehyde dehydrogenase-2 enzyme activity. Moreover, these β-lactams exerted only a transient effect on sucrose drinking, suggesting specificity for chronically inhibiting ethanol reward in adult male P rats. Cerebrospinal fluid concentrations of ampicillin, cefazolin or cefoperazone have been confirmed using high-performance liquid chromatography. These findings demonstrate that multiple β-lactam antibiotics demonstrate efficacy in reducing alcohol consumption and appear to be potential therapeutic compounds for treating alcohol abuse and/or dependence. In addition, these results suggest that pAKT may be an important player in this effect, possibly through increased transcription of GLT-1.
Keywords: Alcohol Drinking; alcohol intake; Aldehyde Dehydrogenase; Ampicillin; Animals; Anti-Bacterial Agents; Body Weight; Cefazolin; Cefoperazone; Central Nervous System Depressants; Conditioning; Drinking; EAAT2; Ethanol; Excitatory Amino Acid Transporter 2; Food Preferences; glutamate; Male; Mitochondria; Mitochondrial; Mitochondrial Proteins; Nucleus Accumbens; Oncogene Protein v-akt; Operant; Prefrontal Cortex; Rats; Sucrose; Sweetening Agents; Time Factors

Epigenetic modulation of brain gene networks for cocaine and alcohol abuse - Farris, Sean P.; Harris, Robert A.; Ponomarev, Igor (Frontiers in Neuroscience, 2015)
Cocaine and alcohol are two substances of abuse that prominently affect the central nervous system (CNS). Repeated exposure to cocaine and alcohol leads to longstanding changes in gene expression, and subsequent functional CNS plasticity, throughout multiple brain regions. Epigenetic modifications of histones are one proposed mechanism guiding these enduring changes to the transcriptome. Characterizing the large number of available biological relationships as network models can reveal unexpected biochemical relationships. Clustering analysis of variation from whole-genome sequencing of gene expression (RNA-Seq) and histone H3 lysine 4 trimethylation (H3K4me3) events (ChIP-Seq) revealed the underlying structure of the transcriptional and epigenomic landscape within hippocampal postmortem brain tissue of drug abusers and control cases. Distinct sets of interrelated networks for cocaine and alcohol abuse were determined for each abusive substance. The network approach identified subsets of functionally related genes that are regulated in agreement with H3K4me3 changes, suggesting cause and effect relationships between this epigenetic mark and gene expression. Gene expression networks consisted of recognized substrates for addiction, such as the dopamine- and cAMP-regulated neuronal phosphoprotein PPP1R1B/DARPP-32 and the vesicular glutamate transporter SLC17A7/VGLUT1 as well as potentially novel molecular targets for substance abuse. Through a systems biology based approach our results illustrate the utility of integrating epigenetic and transcript expression to establish relevant biological networks in the human brain for addiction. Future work with laboratory models may clarify the functional relevance of these gene networks for cocaine and alcohol, and provide a framework for the development of medications for the treatment of addiction.
Keywords: addiction; alcohol; Chromatin; Cocaine; gene co-expression networks

Ethanol activates midkine and anaplastic lymphoma kinase signaling in neuroblastoma cells and in the brain - He, Donghong; Chen, Hu; Muramatsu, Hisako; Lasek, Amy W. (Journal of Neurochemistry, 2015)
Alcohol engages signaling pathways in the brain. Midkine (MDK) is a neurotrophic factor that is over-expressed in the prefrontal cortex of alcoholics. MDK and one of its receptors, anaplastic lymphoma kinase (ALK), also regulate behavioral responses to ethanol in mice. The goal of this study was to determine whether MDK and ALK expression and signaling are activated by ethanol. We found that ethanol treatment of neuroblastoma cells increased MDK and ALK expression. We also assessed activation of ALK by ethanol in cells and found that ALK and ALK-dependent extracellular signal-regulated kinase (ERK) and signal transducer and activator of transcription 3 (STAT3) phosphorylation increased rapidly with ethanol exposure. Similarly, treatment of cells with recombinant MDK protein increased ALK, ERK and STAT3 phosphorylation, suggesting that ethanol may utilize MDK to activate ALK signaling. In support of this, transfection of cells with MDK siRNAs attenuated ALK signaling in response to ethanol. Ethanol also activates ERK signaling in the brain. We found that inhibition of ALK or knockout of MDK attenuated ethanol-induced ERK phosphorylation in mouse amygdala. These results demonstrate that ethanol engages MDK and ALK signaling, which has important consequences for alcohol-induced neurotoxicity and the regulation of behaviors related to alcohol abuse.
Keywords: addiction; alcohol; ALK; Animals; Brain; Cell Line; Enzyme Activation; ERK; Ethanol; Female; Humans; Inbred C57BL; Intercellular Signaling Peptides and Proteins; Knockout; Male; Mice; midkine; Neuroblastoma; Receptor Protein-Tyrosine Kinases; Signal Transduction; STAT3; Tumor

Ethanol and nicotine interaction within the posterior ventral tegmental area in male and female alcohol-preferring rats: evidence of synergy and differential gene activation in the nucleus accumbens shell - Truitt, William A.; Hauser, Sheketha R.; Deehan, Gerald A.; Toalston, Jamie E.; Wilden, Jessica A.; Bell, Richard L.; McBride, William J.; Rodd, Zachary A. (Psychopharmacology, 2015)
RATIONALE: Ethanol and nicotine are frequently co-abused. The biological basis for the high co-morbidity rate is not known. Alcohol-preferring (P) rats will self-administer EtOH or nicotine directly into the posterior ventral tegmental area (pVTA). OBJECTIVE: The current experiments examined whether sub-threshold concentrations of EtOH and nicotine would support the development of self-administration behaviors if the drugs were combined. METHODS: Rats were implanted with a guide cannula aimed at the pVTA. Rats were randomly assigned to groups that self-administered sub-threshold concentrations of EtOH (50 mg%) or nicotine (1 μM) or combinations of ethanol (25 or 50 mg%) and nicotine (0.5 or 1.0 μM). Alterations in gene expression downstream projections areas (nucleus accumbens shell, AcbSh) were assessed following a single, acute exposure to EtOH (50 mg%), nicotine (1 μM), or ethanol and nicotine (50 mg% + 1 μM) directly into the pVTA. RESULTS: The results indicated that P rats would co-administer EtOH and nicotine directly into the pVTA at concentrations that did not support individual self-administration. EtOH and nicotine directly administered into the pVTA resulted in alterations in gene expression in the AcbSh (50.8-fold increase in brain-derived neurotrophic factor (BDNF), 2.4-fold decrease in glial cell line-derived neurotrophic factor (GDNF), 10.3-fold increase in vesicular glutamate transporter 1 (Vglut1)) that were not observed following microinjections of equivalent concentrations/doses of ethanol or nicotine. CONCLUSION: The data indicate that ethanol and nicotine act synergistically to produce reinforcement and alter gene expression within the mesolimbic dopamine system. The high rate of co-morbidity of alcoholism and nicotine dependence could be the result of the interactions of EtOH and nicotine within the mesolimbic dopamine system.
Keywords: alcoholism; Animals; Brain-Derived Neurotrophic Factor; Drug Synergism; Ethanol; Female; Gene Expression; Glial Cell Line-Derived Neurotrophic Factor; Male; Nicotine; Nucleus Accumbens; Random Allocation; Rats; Self Administration; Tobacco Use Disorder; Ventral tegmental area; Vesicular Glutamate Transport Protein 1

Gene expression changes in serotonin, GABA-A receptors, neuropeptides and ion channels in the dorsal raphe nucleus of adolescent alcohol-preferring (P) rats following binge-like alcohol drinking - McClintick, Jeanette N.; McBride, William J.; Bell, Richard L.; Ding, Zheng-Ming; Liu, Yunlong; Xuei, Xiaoling; Edenberg, Howard J. (Pharmacology, Biochemistry, and Behavior, 2015)
Alcohol binge-drinking during adolescence is a serious public health concern with long-term consequences. We used RNA sequencing to assess the effects of excessive adolescent ethanol binge-drinking on gene expression in the dorsal raphe nucleus (DRN) of alcohol preferring (P) rats. Repeated binges across adolescence (three 1h sessions across the dark-cycle per day, 5 days per week for 3 weeks starting at 28 days of age; ethanol intakes of 2.5-3 g/kg/session) significantly altered the expression of approximately one-third of the detected genes. Multiple neurotransmitter systems were altered, with the largest changes in the serotonin system (21 of 23 serotonin-related genes showed decreased expression) and GABA-A receptors (8 decreased and 2 increased). Multiple neuropeptide systems were also altered, with changes in the neuropeptide Y and corticotropin-releasing hormone systems similar to those associated with increased drinking and decreased resistance to stress. There was increased expression of 21 of 32 genes for potassium channels. Expression of downstream targets of CREB signaling was increased. There were also changes in expression of genes involved in inflammatory processes, axonal guidance, growth factors, transcription factors, and several intracellular signaling pathways. These widespread changes indicate that excessive binge drinking during adolescence alters the functioning of the DRN and likely its modulation of many regions of the central nervous system, including the mesocorticolimbic system.
Keywords: Alcohol Drinking; alcoholism; Animals; CREB; Dorsal Raphe Nucleus; GABA-A; GABA-A receptors; Gene Expression Profiling; Inflammation; Ion Channels; Male; Neuropeptides; Rats; Receptors; RNA; Sequence Analysis; Serotonin

Genotypic and sex differences in anxiety-like behavior and alcohol-induced anxiolysis in High Drinking in the Dark selected mice - Barkley-Levenson, Amanda M.; Crabbe, John C. (Alcohol (Fayetteville, N.Y.), 2015)
Alcohol use disorders and anxiety disorders are highly comorbid in humans. In rodent lines selected for alcohol drinking, differences in anxiety-like behavior are also seen. The High Drinking in the Dark (HDID) lines of mice are selectively bred for drinking to intoxication during limited access to alcohol, and these mice represent a genetic model of risk for binge-like drinking. The present studies investigated whether these selected lines differ from control (HS) mice in basal anxiety behavior or in anxiolytic response to alcohol. We also assessed the genetic correlation between alcohol drinking in the dark (DID) and basal anxiety-like behavior using existing inbred strain data. Mice of both sexes and HDID replicates (HDID-1 and HDID-2) were tested on an elevated zero maze immediately following a DID test. In general, HDID mice showed more time spent in the open arms after drinking alcohol than HS mice, and open-arm time was significantly correlated with blood alcohol concentration. HDID-1 male mice also showed less anxiety-like behavior at baseline (water-drinking controls). In a separate experiment, HDID-1 and HS mice were tested for anxiolytic dose-response to acute alcohol injections. Both genotypes showed increasing time spent in the open arms with increasing alcohol doses, and HDID-1 and female mice had greater open-arm time across all doses. HDID-1 control males showed lower anxiety-like behavior than the HS control males. Inbred strain data analysis also showed no significant genetic relationship between alcohol DID and anxiety. These findings suggest that HDID selection has not produced systematic changes in anxiety-like behavior or sensitivity to alcohol-induced anxiolysis, though there is a tendency in the male mice of the first replicate toward reduced basal anxiety-like behavior. Therefore, anxiety state and sensitivity to alcohol's anxiolytic effects do not appear to contribute significantly to the high drinking behavior of the HDID mice.
Keywords: alcohol; Alcohol Drinking; Animals; Anxiety; Behavioral genetics; Binge Drinking; Female; Genotype; Inbred Strains; Male; Mice; selected lines; Sex Characteristics; Species Specificity; Transgenic

GIRK3 gates activation of the mesolimbic dopaminergic pathway by ethanol - Herman, Melissa A.; Sidhu, Harpreet; Stouffer, David G.; Kreifeldt, Max; Le, David; Cates-Gatto, Chelsea; Munoz, Michaelanne B.; Roberts, Amanda J.; Parsons, Loren H.; Roberto, Marisa; Wickman, Kevin; Slesinger, Paul A.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2015)
G protein-gated inwardly rectifying potassium (GIRK) channels are critical regulators of neuronal excitability and can be directly activated by ethanol. Constitutive deletion of the GIRK3 subunit has minimal phenotypic consequences, except in response to drugs of abuse. Here we investigated how the GIRK3 subunit contributes to the cellular and behavioral effects of ethanol, as well as to voluntary ethanol consumption. We found that constitutive deletion of GIRK3 in knockout (KO) mice selectively increased ethanol binge-like drinking, without affecting ethanol metabolism, sensitivity to ethanol intoxication, or continuous-access drinking. Virally mediated expression of GIRK3 in the ventral tegmental area (VTA) reversed the phenotype of GIRK3 KO mice and further decreased the intake of their wild-type counterparts. In addition, GIRK3 KO mice showed a blunted response of the mesolimbic dopaminergic (DA) pathway to ethanol, as assessed by ethanol-induced excitation of VTA neurons and DA release in the nucleus accumbens. These findings support the notion that the subunit composition of VTA GIRK channels is a critical determinant of DA neuron sensitivity to drugs of abuse. Furthermore, our study reveals the behavioral impact of this cellular effect, whereby the level of GIRK3 expression in the VTA tunes ethanol intake under binge-type conditions: the more GIRK3, the less ethanol drinking.
Keywords: alcohol; Analysis of Variance; Animals; Binge Drinking; DNA Primers; Dopaminergic Neurons; Ethanol; G Protein-Coupled Inwardly-Rectifying Potassium Channels; In Situ Hybridization; Inbred C57BL; Ion Channel Gating; Kcnj9; Kir3.3; Knockout; Mice; Microdialysis; Motivation; Reverse Transcriptase Polymerase Chain Reaction; Reward; ventral midbrain

Glycine receptors containing α2 or α3 subunits regulate specific ethanol-mediated behaviors - Blednov, Yuri A.; Benavidez, Jillian M.; Black, Mendy; Leiter, Courtney R.; Osterndorff-Kahanek, Elizabeth; Harris, R. Adron (The Journal of Pharmacology and Experimental Therapeutics, 2015)
Glycine receptors (GlyRs) are broadly expressed in the central nervous system. Ethanol enhances the function of brain GlyRs, and the GlyRα1 subunit is associated with some of the behavioral actions of ethanol, such as loss of righting reflex. The in vivo role of GlyRα2 and α3 subunits in alcohol responses has not been characterized despite high expression levels in the nucleus accumbens and amygdala, areas that are important for the rewarding properties of drugs of abuse. We used an extensive panel of behavioral tests to examine ethanol actions in mice lacking Glra2 (the gene encoding the glycine receptor alpha 2 subunit) or Glra3 (the gene encoding the glycine receptor alpha 3 subunit). Deletion of Glra2 or Glra3 alters specific ethanol-induced behaviors. Glra2 knockout mice demonstrate reduced ethanol intake and preference in the 24-hour two-bottle choice test and increased initial aversive responses to ethanol and lithium chloride. In contrast, Glra3 knockout mice show increased ethanol intake and preference in the 24-hour intermittent access test and increased development of conditioned taste aversion to ethanol. Mutants and wild-type mice consumed similar amounts of ethanol in the limited access drinking in the dark test. Other ethanol effects, such as anxiolysis, motor incoordination, loss of righting reflex, and acoustic startle response, were not altered in the mutants. The behavioral changes in mice lacking GlyRα2 or α3 subunits were distinct from effects previously observed in mice with knock-in mutations in the α1 subunit. We provide evidence that GlyRα2 and α3 subunits may regulate ethanol consumption and the aversive response to ethanol.
Keywords: Animal; Animals; Avoidance Learning; Behavior; Brain; Drinking Behavior; Ethanol; Food Preferences; Glycine; Knockout; Messenger; Mice; Motor Activity; Mutation; Receptors; Reflex; RNA; Startle

Homer2 within the nucleus accumbens core bidirectionally regulates alcohol intake by both P and Wistar rats - Haider, Arshad; Woodward, Nicholas C.; Lominac, Kevin D.; Sacramento, Arianne D.; Klugmann, Matthias; Bell, Richard L.; Szumlinski, Karen K. (Alcohol (Fayetteville, N.Y.), 2015)
In murine models of alcoholism, the glutamate receptor scaffolding protein Homer2 bidirectionally regulates alcohol intake. Although chronic alcohol drinking increases Homer2 expression within the core subregion of the nucleus accumbens (NAc) of alcohol-preferring P rats, the relevance of this neuroadaptation for alcohol intake has yet to be determined in rats. Thus, the present study employed an adeno-associated viral vector (AAV) strategy to over-express and knock down the major rodent isoform Homer2b within the NAc of both P and outbred Wistar rats to examine for changes in alcohol preference and intake (0-30% v/v) under continuous-access procedures. The generalization of AAV effects to non-drug, palatable, sweet solutions was also determined in tests of sucrose (0-5% w/v) and saccharin (0-0.125% w/v) intake/preference. No net-flux in vivo microdialysis was conducted for glutamate in the NAc to relate Homer2-dependent changes in alcohol intake to extracellular levels of glutamate. Line differences were noted for sweet solution preference and intake, but these variables were not affected by intra-NAc AAV infusion in either line. In contrast, Homer2b over-expression elevated, while Homer2b knock-down reduced, alcohol intake in both lines, and this effect was greatest at the highest concentration. Strikingly, in P rats there was a direct association between changes in Homer2b expression and NAc extracellular glutamate levels, but this effect was not seen in Wistar rats. These data indicate that NAc Homer2b expression actively regulates alcohol consumption by rats, paralleling this previous observation in mice. Overall, these findings underscore the importance of mesocorticolimbic glutamate activity in alcohol abuse/dependence and suggest that Homer2b and/or its constituents may serve as molecular targets for the treatment of these disorders.
Keywords: AAV; Alcohol Drinking; Alcohol preference; Animals; Carrier Proteins; glutamate; Homer Scaffolding Proteins; Homer2; Male; Microdialysis; Nucleus Accumbens; P rat; Rats; Wistar

Hypocretin receptor 2 antagonism dose-dependently reduces escalated heroin self-administration in rats - Schmeichel, Brooke E.; Barbier, Estelle; Misra, Kaushik K.; Contet, Candice; Schlosburg, Joel E.; Grigoriadis, Dimitri; Williams, John P.; Karlsson, Camilla; Pitcairn, Caleb; Heilig, Markus; Koob, George F.; Vendruscolo, Leandro F. (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2015)
The hypocretin/orexin (HCRT) system has been associated with both positive and negative drug reinforcement, implicating HCRT receptor 1 (HCRT-R1) signaling in drug-related behaviors for all major drug classes, including opioids. However, to date there are limited studies investigating the role of HCRT receptor 2 (HCRT-R2) signaling in compulsive-like drug seeking. Escalation of drug intake with extended access has been suggested to model the transition from controlled drug use to compulsive-like drug seeking/taking. The current study examined the effects of a HCRT-R2 antagonist, NBI-80713, on heroin self-administration in rats allowed short- (1 h; ShA) or long- (12 h; LgA) access to intravenous heroin self-administration. Results indicate that systemically administered NBI-80713 dose-dependently decreased heroin self-administration in LgA, but not in ShA, animals. Quantitative PCR analyses showed an increase in Hcrtr2 mRNA levels in the central amygdala, a stress-related brain region, of LgA rats. These observations suggest a functional role for HCRT-R2 signaling in compulsive-like heroin self-administration associated with extended access and indicate HCRT-R2 antagonism as a potential pharmacological target for the treatment of heroin dependence.
Keywords: Animal; Animals; Central Amygdaloid Nucleus; Disease Models; Dose-Response Relationship; Drinking Behavior; Drug; Drug-Seeking Behavior; FEEDING BEHAVIOR; Heroin; Heroin Dependence; Locomotion; Male; Messenger; Narcotics; Orexin Receptor Antagonists; Orexin Receptors; Rats; RNA; Self Administration; Substance Withdrawal Syndrome; Time Factors; Wistar

Ibudilast reduces alcohol drinking in multiple animal models of alcohol dependence - Bell, Richard L.; Lopez, Marcelo F.; Cui, Changhai; Egli, Mark; Johnson, Kirk W.; Franklin, Kelle M.; Becker, Howard C. (Addiction Biology, 2015)
Neuroinflammatory signaling pathways in the central nervous system are of current interest as potential pharmacotherapy targets for alcohol dependence. In this study, we examined the ability of ibudilast, a non-selective phosphodiesterase inhibitor, to reduce alcohol drinking and relapse in alcohol-preferring P rats, high-alcohol drinking HAD1 rats, and in mice made dependent on alcohol through cycles of alcohol vapor exposure. When administered twice daily, ibudilast reduced alcohol drinking in rats by approximately 50% and reduced drinking by alcohol-dependent mice at doses which had no effect in non-dependent mice. These findings support the viability of ibudilast as a possible treatment for alcohol dependence.
Keywords: alcohol; Alcohol dependence; Alcohol Drinking; Alcohol preference; alcoholism; Animal; Animals; AV-411; Behavior; Disease Models; Ethanol; ibudilast; Male; Mice; MN-166; Neuroimmune; phosphodiesterase; Phosphodiesterase Inhibitors; Pyridines; Rats

Identifying candidate drivers of alcohol dependence-induced excessive drinking by assembly and interrogation of brain-specific regulatory networks - Repunte-Canonigo, Vez; Shin, William; Vendruscolo, Leandro F.; Lefebvre, Celine; van der Stap, Lena; Kawamura, Tomoya; Schlosburg, Joel E.; Alvarez, Mariano; Koob, George F.; Califano, Andrea; Sanna, Pietro Paolo (Genome Biology, 2015)
BACKGROUND: A systems biology approach based on the assembly and interrogation of gene regulatory networks, or interactomes, was used to study neuroadaptation processes associated with the transition to alcohol dependence at the molecular level. RESULTS: Using a rat model of dependent and non-dependent alcohol self-administration, we reverse engineered a global transcriptional regulatory network during protracted abstinence, a period when relapse rates are highest. We then interrogated the network to identify master regulator genes that mechanistically regulate brain region-specific signatures associated with dependent and non-dependent alcohol self-administration. Among these, the gene coding for the glucocorticoid receptor was independently identified as a master regulator in multiple brain regions, including the medial prefrontal cortex, nucleus accumbens, central nucleus of the amygdala, and ventral tegmental area, consistent with the view that brain reward and stress systems are dysregulated during protracted abstinence. Administration of the glucocorticoid antagonist mifepristone in either the nucleus accumbens or ventral tegmental area selectively decreased dependent, excessive, alcohol self-administration in rats but had no effect on non-dependent, moderate, alcohol self-administration. CONCLUSIONS: Our study suggests that assembly and analysis of regulatory networks is an effective strategy for the identification of key regulators of long-term neuroplastic changes within specific brain regions that play a functional role in alcohol dependence. More specifically, our results support a key role for regulatory networks downstream of the glucocorticoid receptor in excessive alcohol drinking during protracted alcohol abstinence.
Keywords: alcoholism; Algorithms; Animals; Brain; Ethanol; Gene Regulatory Networks; Genes; Glucocorticoid; Hormone Antagonists; Mifepristone; Rats; Receptors; Regulator; Self Administration

IL-1 interacts with ethanol effects on GABAergic transmission in the mouse central amygdala - Bajo, Michal; Varodayan, Florence P.; Madamba, Samuel G.; Robert, Amanda J.; Casal, Lindsey M.; Oleata, Christopher S.; Siggins, George R.; Roberto, Marisa (Frontiers in Pharmacology, 2015)
Neuroinflammation is hypothesized to enhance alcohol consumption and contribute to the development of alcoholism. GABAergic transmission in the central amygdala (CeA) plays an important role in the transition to alcohol dependence. Therefore, we studied the effects of interleukin-1β (IL-1β), a proinflammatory cytokine mediating ethanol-induced neuroinflammation, and its interaction with ethanol on CeA GABAegic transmission in B6129SF2/J mice. We also assessed ethanol intake in B6129SF2/J mice. Intake with unlimited (24 h) ethanol access was 9.2-12.7 g/kg (3-15% ethanol), while limited (2 h) access produced an intake of 4.1 ± 0.5 g/kg (15% ethanol). In our electrophysiology experiments, we found that recombinant IL-1β (50 and 100 ng/ml) significantly decreased the amplitude of evoked inhibitory postsynaptic potentials (eIPSPs), with no significant effects on paired-pulse facilitation (PPF). IL-1β (50 ng/ml) had dual effects on spontaneous miniature inhibitory postsynaptic currents (mIPSCs): increasing mIPSC frequencies in most CeA neurons, but decreasing both mIPSC frequencies and amplitudes in a few cells. The IL-1β receptor antagonist (IL-1ra; 100 ng/ml) also had dual effects on mIPSCs and prevented the actions of IL-1β on mIPSC frequencies. These results suggest that IL-1β can alter CeA GABAergic transmission at pre- and postsynaptic sites. Ethanol (44 mM) significantly increased eIPSP amplitudes, decreased PPFs, and increased mIPSC frequencies. IL-1β did not alter ethanol's enhancement of the eIPSP amplitude, but, in IL-1β-responsive neurons, the ethanol effects on mIPSC frequencies were lost. Overall, our data suggest that the IL-1 system is involved in basal GABAergic transmission and that IL-1β interacts with the ethanol-induced facilitation of CeA GABAergic transmission.
Keywords: central amygdala; Cytokine; eIPSPs; GABAA; IL-1ra; IL-1β; interleukin; IPSCs

The importance of animals in advancing research on alcohol use disorders - Helms, Christa M.; Bell, Richard L.; Bennett, Allyson J.; Davies, Daryl L.; Chester, Julia A.; Kosten, Therese A.; Leeman, Robert F.; Panicker, Sangeeta; Platt, Donna M.; Weiner, Jeff L.; Edwards, Scott (Alcoholism, Clinical and Experimental Research, 2015)
Keywords: Alcohol-Related Disorders; Animal; Animals; Disease Models; research

Increased alcohol consumption in urocortin 3 knockout mice is unaffected by chronic inflammatory pain - Smith, Monique L.; Li, Ju; Ryabinin, Andrey E. (Alcohol and Alcoholism (Oxford, Oxfordshire), 2015)
AIMS: Stress neurocircuitry may modulate the relationship between alcohol drinking and chronic pain. The corticotropin-releasing factor (CRF) system is crucial for regulation of stress responses. The current study aimed to elucidate the role of the endogenous CRF ligand Urocortin 3 (Ucn3) in the relationship between alcohol drinking behavior and chronic pain using a genetic approach. METHODS: Ucn3 (KO) and wildtype (WT) littermates were subjected to a 24-h access drinking procedure prior to and following induction of chronic inflammatory pain. RESULTS: Ucn3 KO mice displayed significantly increased ethanol intake and preference compared with WT across the time course. There were no long-term effects of chronic pain on alcohol drinking behavior, regardless of genotype, nor any evidence for alcohol-induced analgesia. CONCLUSION: The increased drinking in Ucn3 KO supports a role for this peptide in alcohol-related behavior. These data suggest the necessity for more research exploring the relationship between alcohol drinking, chronic pain and the CRF system in rodent models.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Choice Behavior; Chronic Pain; Female; Inflammation; Knockout; Male; Mice; Psychological; Stress; Urocortins

Influence of sex on genetic regulation of "drinking in the dark" alcohol consumption - Vanderlinden, Lauren A.; Saba, Laura M.; Bennett, Beth; Hoffman, Paula L.; Tabakoff, Boris (Mammalian Genome: Official Journal of the International Mammalian Genome Society, 2015)
The ILSXISS (LXS) recombinant inbred (RI) panel of mice is a valuable resource for genetic mapping studies of complex traits, due to its genetic diversity and large number of strains. Male and female mice from this panel were used to investigate genetic influences on alcohol consumption in the "drinking in the dark" (DID) model. Male mice (38 strains) and female mice (36 strains) were given access to 20% ethanol during the early phase of their circadian dark cycle for four consecutive days. The first principal component of alcohol consumption measures on days 2, 3, and 4 was used as a phenotype (DID phenotype) to calculate QTLs, using a SNP marker set for the LXS RI panel. Five QTLs were identified, three of which included a significant genotype by sex interaction, i.e., a significant genotype effect in males and not females. To investigate candidate genes associated with the DID phenotype, data from brain microarray analysis (Affymetrix Mouse Exon 1.0 ST Arrays) of male LXS RI strains were combined with RNA-Seq data (mouse brain transcriptome reconstruction) from the parental ILS and ISS strains in order to identify expressed mouse brain transcripts. Candidate genes were determined based on common eQTL and DID phenotype QTL regions and correlation of transcript expression levels with the DID phenotype. The resulting candidate genes (in particular, Arntl/Bmal1) focused attention on the influence of circadian regulation on the variation in the DID phenotype in this population of mice.
Keywords: Alcohol Drinking; Animals; Aryl Hydrocarbon Receptor Nuclear Translocator; Base Sequence; Brain; Circadian Rhythm; Darkness; Female; Genetic Association Studies; Genotype; High-Throughput Nucleotide Sequencing; Inbred Strains; Male; Mice; Microarray Analysis; Molecular Sequence Data; Phenotype; Polymorphism; Principal Component Analysis; Quantitative Trait Loci; Sex Factors; Single Nucleotide

Interaction of CRF and kappa opioid systems on GABAergic neurotransmission in the mouse central amygdala - Kang-Park, Maenghee; Kieffer, Brigitte L.; Roberts, Amanda J.; Siggins, George R.; Moore, Scott D. (The Journal of Pharmacology and Experimental Therapeutics, 2015)
{The corticotropin-releasing factor (CRF) and kappa-opioid receptor (KOR) systems are both implicated in stress-related behaviors and drug dependence. Although previous studies suggest that antagonism of each system blocks aspects of experimental models of drug dependence, the possible interaction between these systems at the neuronal level has not been completely examined. We used an in vitro brain slice preparation to investigate the interaction of these two peptide systems on inhibitory neurotransmission in the central nucleus of the amygdala (CeA). Application of exogenous CRF increased the mean frequency of GABAergic miniature inhibitory postsynaptic currents (mIPSC) by 20.2%, suggesting an increase in presynaptic GABA release. Although the pharmacological blockade of KORs by norBNI alone did not significantly affect mIPSC frequency, it significantly enhanced the effect of CRF (by 43.9%
Keywords: Animals; Central Amygdaloid Nucleus; Corticotropin-Releasing Hormone; gamma-Aminobutyric Acid; Inbred C57BL; Inhibitory Postsynaptic Potentials; kappa; Knockout; Mice; Miniature Postsynaptic Potentials; Naltrexone; Opioid; Receptors; Synaptic Transmission

Involvement of Purinergic P2X4 Receptors in Alcohol Intake of High-Alcohol-Drinking (HAD) Rats - Franklin, Kelle M.; Hauser, Sheketha R.; Lasek, Amy W.; Bell, Richard L.; McBride, William J. (Alcoholism, Clinical and Experimental Research, 2015)
BACKGROUND: The P2X4 receptor (P2X4R) is thought to be involved in regulating alcohol-consuming behaviors, and ethanol (EtOH) has been reported to inhibit P2X4Rs. Ivermectin is an antiparasitic agent that acts as a positive allosteric modulator of the P2X4R. This study examined the effects of systemically and centrally administered ivermectin on alcohol drinking of replicate lines of high-alcohol-drinking (HAD-1/HAD-2) rats, and the effects of lentiviral-delivered short-hairpin RNAs (shRNAs) targeting P2rx4 on EtOH intake of female HAD-2 rats. METHODS: For the first experiment, adult male HAD-1 and HAD-2 rats were given 24-hour free-choice access to 15% EtOH versus water. Dose-response effects of ivermectin (1.5 to 7.5 mg/kg, intraperitoneally [i.p.]) on EtOH intake were determined; the effects of ivermectin were then examined for 2% w/v sucrose intake over 5 consecutive days. In the second experiment, female HAD-2 rats were trained to consume 15% EtOH under 2-hour limited access conditions, and dose-response effects of intracerebroventricular (ICV) administration of ivermectin (0.5 to 2.0 μg) were determined over 5 consecutive days. The third experiment determined the effects of microinfusion of a lentivirus expressing P2rx4 shRNAs into the posterior ventral tegmental area (VTA) on 24-hour EtOH free-choice drinking of female HAD-2 rats. RESULTS: The highest i.p. dose of ivermectin reduced alcohol drinking (30 to 45%) in both rat lines, but did not alter sucrose intake. HAD-2 rats appeared to be more sensitive than HAD-1 rats to the effects of ivermectin. ICV administration of ivermectin reduced 2-hour limited access intake (~35%) of female HAD-2 rats; knockdown of P2rx4 expression in the posterior VTA reduced 24-hour free-choice EtOH intake (~20%). CONCLUSIONS: Overall, the results of this study support a role for P2X4Rs within the mesolimbic system in mediating alcohol-drinking behavior.
Keywords: Alcohol Drinking; Animals; Dose-Response Relationship; Drug; Female; High-Alcohol-Drinking Rats; Inbred Strains; Infusions; Intraventricular; Ivermectin; Male; p2rx4; P2X4 receptor; Purinergic P2X Receptor Agonists; Purinergic P2X Receptor Antagonists; Purinergic P2X4; Rats; Receptors; RNA; Small Interfering; Ventral tegmental area

Knockdown of ventral tegmental area mu-opioid receptors in rats prevents effects of social defeat stress: implications for amphetamine cross-sensitization, social avoidance, weight regulation and expression of brain-derived neurotrophic factor - Johnston, Caitlin E.; Herschel, Daniel J.; Lasek, Amy W.; Hammer, Ronald P.; Nikulina, Ella M. (Neuropharmacology, 2015)
Social defeat stress causes social avoidance and long-lasting cross-sensitization to psychostimulants, both of which are associated with increased brain-derived neurotrophic factor (BDNF) expression in the ventral tegmental area (VTA). Moreover, social stress upregulates VTA mu-opioid receptor (MOR) mRNA. In the VTA, MOR activation inhibits GABA neurons to disinhibit VTA dopamine neurons, thus providing a role for VTA MORs in the regulation of psychostimulant sensitization. The present study determined the effect of lentivirus-mediated MOR knockdown in the VTA on the consequences of intermittent social defeat stress, a salient and profound stressor in humans and rodents. Social stress exposure induced social avoidance and attenuated weight gain in animals with non-manipulated VTA MORs, but both these effects were prevented by VTA MOR knockdown. Rats with non-manipulated VTA MOR expression exhibited cross-sensitization to amphetamine challenge (1.0 mg/kg, i.p.), evidenced by a significant augmentation of locomotion. By contrast, knockdown of VTA MORs prevented stress-induced cross-sensitization without blunting the locomotor-activating effects of amphetamine. At the time point corresponding to amphetamine challenge, immunohistochemical analysis was performed to examine the effect of stress on VTA BDNF expression. Prior stress exposure increased VTA BDNF expression in rats with non-manipulated VTA MOR expression, while VTA MOR knockdown prevented stress-induced expression of VTA BDNF. Taken together, these results suggest that upregulation of VTA MOR is necessary for the behavioral and biochemical changes induced by social defeat stress. Elucidating VTA MOR regulation of stress effects on the mesolimbic system may provide new therapeutic targets for treating stress-induced vulnerability to substance abuse.
Keywords: Amphetamine; Analgesics; Animal; Animals; Body Weight; Brain-Derived Neurotrophic Factor; Cell Count; Central Nervous System Stimulants; Disease Models; Escape Reaction; Genetic; Handling (Psychology); Long-Evans; Male; Motor Activity; mu; Opioid; Protein Binding; Psychological; Rats; Receptors; Sprague-Dawley; Stress; Transduction; Ventral tegmental area

Nf1 regulates alcohol dependence-associated excessive drinking and gamma-aminobutyric acid release in the central amygdala in mice and is associated with alcohol dependence in humans - Repunte-Canonigo, Vez; Herman, Melissa A.; Kawamura, Tomoya; Kranzler, Henry R.; Sherva, Richard; Gelernter, Joel; Farrer, Lindsay A.; Roberto, Marisa; Sanna, Pietro Paolo (Biological Psychiatry, 2015)
BACKGROUND: The neurofibromatosis type 1 (Nf1) gene encodes a GTPase activating protein that negatively regulates small GTPases of the Ras family. METHODS: We assessed alcohol-related behaviors including alcohol sensitivity, dependent and nondependent drinking, and basal and alcohol-induced gamma-aminobutyric acid (GABA) release in the central nucleus of the amygdala (CeA) in Nf1 heterozygous null mice (Nf1(+/-)). We also investigated the associations of NF1 polymorphisms with alcohol dependence risk and severity in humans. RESULTS: Nf1(+/-) mice do not differ from wild-type mice in nondependent drinking, such as 24-hour, 2-bottle choice drinking in the dark binge drinking or limited access 2-bottle choice. However, Nf1(+/-) mice failed to escalate alcohol drinking following chronic intermittent ethanol vapor exposure (CIE) to induce dependence. Alcohol acutely increases GABA release in the CeA and alcohol dependence is characterized by increased baseline GABA release in CeA. Interestingly, GABA release in Nf1(+/-) mice is greater at baseline than wild-type mice, is not elevated by induction of dependence by CIE, and failed to show alcohol-induced facilitation both before and after CIE. Additionally, we observed that multiple variants in the human NF1 gene are associated with a quantitative measure of alcohol dependence in both African Americans and European Americans. CONCLUSIONS: In this translational investigation, we found that Nf1 activity regulates excessive drinking and basal and ethanol-stimulated GABA release in the mouse central amygdala. We also found that genetic variation in NF1 may confer an inherent susceptibility to the transition from nondependent to dependent drinking in humans.
Keywords: Alcohol dependence; Alcohol Drinking; alcoholism; Amygdala; Animals; Central Amygdaloid Nucleus; Electrophysiology; Ethanol; GABA; gamma-Aminobutyric Acid; Genes; Genetic association; Humans; Inbred C57BL; Mice; Miniature Postsynaptic Potentials; Neurofibromatosis 1; Neurons; Polymorphism; Presynaptic mechanisms; Single Nucleotide

A novel anxiogenic role for the delta opioid receptor expressed in GABAergic forebrain neurons - Chu Sin Chung, Paul; Keyworth, Helen L.; Martin-Garcia, Elena; Charbogne, Pauline; Darcq, Emmanuel; Bailey, Alexis; Filliol, Dominique; Matifas, Audrey; Scherrer, Grégory; Ouagazzal, Abdel-Mouttalib; Gaveriaux-Ruff, Claire; Befort, Katia; et al. (Biological Psychiatry, 2015)
BACKGROUND: The delta opioid receptor (DOR) is broadly expressed throughout the nervous system; it regulates chronic pain, emotional responses, motivation, and memory. Neural circuits underlying DOR activities have been poorly explored by genetic approaches. We used conditional mouse mutagenesis to elucidate receptor function in GABAergic neurons of the forebrain. METHODS: We characterized DOR distribution in the brain of Dlx5/6-CreXOprd1(fl/fl) (Dlx-DOR) mice and tested main central DOR functions through behavioral testing. RESULTS: The DOR proteins were strongly deleted in olfactory bulb and striatum and remained intact in cortex and basolateral amygdala. Olfactory perception, circadian activity, and despair-like behaviors were unchanged. In contrast, locomotor stimulant effects of SNC80 (DOR agonist) and SKF81297 (D1 agonist) were abolished and increased, respectively. The Dlx-DOR mice showed lower levels of anxiety in the elevated plus maze, opposing the known high anxiety in constitutive DOR knockout animals. Also, Dlx-DOR mice reached the food more rapidly in a novelty suppressed feeding task, despite their lower motivation for food reward observed in an operant paradigm. Finally, c-fos protein staining after novelty suppressed feeding was strongly reduced in amygdala, concordant with the low anxiety phenotype of Dlx-DOR mice. CONCLUSIONS: We demonstrate that DORs expressed in the forebrain mediate the described locomotor effect of SNC80 and inhibit D1-stimulated hyperactivity. Our data also reveal an unanticipated anxiogenic role for this particular DOR subpopulation, with a potential novel adaptive role. In emotional responses, DORs exert dual anxiolytic and anxiogenic roles, both of which may have implications in the area of anxiety disorders.
Keywords: Animal; Animals; Anxiety; Behavior; Benzamides; Benzazepines; Brain; Conditional gene knockout; Corpus Striatum; delta; Delta opioid receptor; Dopamine Agonists; Dopamine D1; Emotion; Female; GABAergic forebrain neurons; GABAergic Neurons; Knockout; Locomotion; Male; Messenger; Mice; Motivation; Motor Activity; olfactory bulb; Opioid; Piperazines; Prosencephalon; Proto-Oncogene Proteins c-fos; Receptors; RNA

Peroxisome proliferator-activated receptors α and γ are linked with alcohol consumption in mice and withdrawal and dependence in humans - Blednov, Yuri A.; Benavidez, Jillian M.; Black, Mendy; Ferguson, Laura B.; Schoenhard, Grant L.; Goate, Alison M.; Edenberg, Howard J.; Wetherill, Leah; Hesselbrock, Victor; Foroud, Tatiana; Harris, R. Adron (Alcoholism, Clinical and Experimental Research, 2015)
BACKGROUND: Peroxisome proliferator-activated receptor (PPAR) agonists reduce voluntary ethanol (EtOH) consumption in rat models and are promising therapeutics in the treatment for drug addictions. We studied the effects of different classes of PPAR agonists on chronic EtOH intake and preference in mice with a genetic predisposition for high alcohol consumption and then examined human genomewide association data for polymorphisms in PPAR genes in alcohol-dependent subjects. METHODS: Two different behavioral tests were used to measure intake of 15% EtOH in C57BL/6J male mice: 24-hour 2-bottle choice and limited access (3-hour) 2-bottle choice, drinking in the dark. We measured the effects of pioglitazone (10 and 30 mg/kg), fenofibrate (50 and 150 mg/kg), GW0742 (10 mg/kg), tesaglitazar (1.5 mg/kg), and bezafibrate (25 and 75 mg/kg) on EtOH intake and preference. Fenofibric acid, the active metabolite of fenofibrate, was quantified in mouse plasma, liver, and brain by liquid chromatography tandem mass spectrometry. Data from a human genome-wide association study (GWAS) completed in the Collaborative Study on the Genetics of Alcoholism (COGA) were then used to analyze the association of single nucleotide polymorphisms (SNPs) in different PPAR genes (PPARA, PPARD, PPARG, and PPARGC1A) with 2 phenotypes: DSM-IV alcohol dependence (AD) and the DSM-IV criterion of withdrawal. RESULTS: Activation of 2 isoforms of PPARs, α and γ, reduced EtOH intake and preference in the 2 different consumption tests in mice. However, a selective PPARδ agonist or a pan agonist for all 3 PPAR isoforms did not decrease EtOH consumption. Fenofibric acid, the active metabolite of the PPARα agonist fenofibrate, was detected in liver, plasma, and brain after 1 or 8 days of oral treatment. The GWAS from COGA supported an association of SNPs in PPARA and PPARG with alcohol withdrawal and PPARGC1A with AD but found no association for PPARD with either phenotype. CONCLUSIONS: We provide convergent evidence using both mouse and human data for specific PPARs in alcohol action. Reduced EtOH intake in mice and the genetic association between AD or withdrawal in humans highlight the potential for repurposing FDA-approved PPARα or PPARγ agonists for the treatment of AD.
Keywords: Adult; Alcohol Drinking; alcoholism; Alkanesulfonates; Animals; Bezafibrate; Brain; C57BL/6J; Female; Fenofibrate; Fenofibric Acid; Genome-Wide Association Study; Humans; Liver; Male; Mice; Phenylpropionates; Pioglitazone; Polymorphism; PPAR alpha; PPAR gamma; Single Nucleotide; Tesag-litazar; Thiazoles; Thiazolidinediones; Two-bottle choice

Quantitative trait locus mapping of acute functional tolerance in the LXS recombinant inbred strains - Bennett, Beth; Larson, Colin; Richmond, Phillip A.; Odell, Aaron T.; Saba, Laura M.; Tabakoff, Boris; Dowell, Robin; Radcliffe, Richard A. (Alcoholism, Clinical and Experimental Research, 2015)
BACKGROUND: We previously reported that acute functional tolerance (AFT) to the hypnotic effects of alcohol was significantly correlated with drinking in the dark (DID) in the LXS recombinant inbred panel, but only in mice that had been pretreated with alcohol. Here, we have conducted quantitative trait locus (QTL) mapping for AFT. DNA sequencing of the progenitor ILS and ISS strains and microarray analyses were also conducted to identify candidate genes and functional correlates. METHODS: LXS mice were given either saline or alcohol (5 g/kg) on day 1 and then tested for loss of righting reflex AFT on day 2. QTLs were mapped using standard procedures. Two microarray analyses from brain were conducted: (i) naïve LXS mice and (ii) an alcohol treatment time course in the ILS and ISS. The full genomes of the ILS and ISS were sequenced to a depth of approximately 30×. RESULTS: A significant QTL for AFT in the alcohol pretreatment group was mapped to distal chromosome 4; numerous suggestive QTLs were also mapped. Preference drinking and DID have previously been mapped to the chromosome 4 locus. The credible interval of the significant chromosome 4 QTL spanned 23 Mb and included 716 annotated genes of which 150 had at least 1 nonsynonymous single nucleotide polymorphism or small indel that differed between the ILS and ISS; expression of 48 of the genes was cis-regulated. Enrichment analysis indicated broad functional categories underlying AFT, including proteolysis, transcription regulation, chromatin modification, protein kinase activity, and apoptosis. CONCLUSIONS: The chromosome 4 QTL is a key region containing possibly pleiotropic genes for AFT and drinking behavior. Given that the region contains many viable candidates and a large number of the genes in the interval fall into 1 or more of the enriched functional categories, we postulate that many genes of varying effect size contribute to the observed QTL effect.
Keywords: Acute Functional Tolerance; Alcohol Drinking; alcoholism; Animals; Brain; Chromosome Mapping; Deep Sequencing; Drug Tolerance; Ethanol; Gene Expression Profiling; Genetic Association Studies; Genetics; Genotype; Inbred Strains; Male; Mice; Microarray; Mouse; Quantitative Trait Loci; Quantitative Trait Locus; Reflex; Righting

Reduction of alcohol drinking of alcohol-preferring (P) and high-alcohol drinking (HAD1) rats by targeting phosphodiesterase-4 (PDE4) - Franklin, Kelle M.; Hauser, Sheketha R.; Lasek, Amy W.; McClintick, Jeanette; Ding, Zheng-Ming; McBride, William J.; Bell, Richard L. (Psychopharmacology, 2015)
RATIONALE: Phosphodiesterase-4 (PDE4) and neuroimmune signaling have been posited to regulate alcohol drinking. OBJECTIVES: This study evaluated the involvement of PDE4 and Il22ra2 on ethanol (EtOH) intake by alcohol-preferring (P) and high-alcohol-drinking (HAD1) rats. METHODS: Exp 1 determined the dose-response effects of PDE4 inhibitors, rolipram, and Ro 20-1724, on 2 h/day free-choice EtOH intake by adult P and HAD1 rats. Exps 2-3 examined the effects of repeated administration with the PDE4 inhibitors on EtOH or sucrose intake and locomotor behavior. Exp 4 determined Pde4-associated gene expression differences in subregions of the extended amygdala, between high- and low-alcohol-consuming rat lines. Exp 5 evaluated the effects of infusing short hairpin RNA to knock down Il22ra2 in the nucleus accumbens (NAc) shell on a 24-h free-choice EtOH drinking by P rats. RESULTS: Administration of rolipram or Ro 20-1724 reduced EtOH intake by P rats; Ro 20-1724 reduced EtOH intake by HAD1 rats. Repeated rolipram or Ro 20-1724 exposure reduced EtOH intake by P and HAD1 rats. PDE4 inhibition induced motor impairment during the first hour of EtOH intake by P rats. Higher gene expression levels for PDE4A were found in the NAc shell of P vs NP rats. ShRNAs targeting Il22ra2 in the NAc shell significantly reduced chronic EtOH intake. CONCLUSIONS: PDE4 and neuroinflammatory/immune signaling pathways could represent molecular targets for the treatment of alcohol use disorders in genetically predisposed subjects. This study underscores the importance of testing compounds over multiple days and rat lines when determining efficacy to disrupt excessive alcohol intake.
Keywords: Alcohol Drinking; Alcohol preference; animal model; Animals; Cyclic Nucleotide Phosphodiesterases; Dose-Response Relationship; Drug; Drug Delivery Systems; Ethanol; Female; Genetic predisposition; High-alcohol consuming; Interleukin 22 receptor; Male; Nucleus Accumbens; Phosphodiesterase 4 Inhibitors; Rats; Rolipram; Selective breeding; Species Specificity; Type 4

The reinforcing properties of ethanol are quantitatively enhanced in adulthood by peri-adolescent ethanol, but not saccharin, consumption in female alcohol-preferring (P) rats - Toalston, Jamie E.; Deehan, Gerald A.; Hauser, Sheketha R.; Engleman, Eric A.; Bell, Richard L.; Murphy, James M.; McBride, William J.; Rodd, Zachary A. (Alcohol (Fayetteville, N.Y.), 2015)
Alcohol drinking during adolescence is associated in adulthood with heavier alcohol drinking and an increased rate of alcohol dependence. Past research in our laboratory has indicated that peri-adolescent ethanol consumption can enhance the acquisition and reduce the rate of extinction of ethanol self-administration in adulthood. Caveats of the past research include reinforcer specificity, increased oral consumption during peri-adolescence, and a lack of quantitative assessment of the reinforcing properties of ethanol. The current experiments were designed to determine the effects of peri-adolescent ethanol or saccharin drinking on acquisition and extinction of oral ethanol self-administration and ethanol seeking, and to quantitatively assess the reinforcing properties of ethanol (progressive ratio). Ethanol or saccharin access by alcohol-preferring (P) rats occurred during postnatal day (PND) 30-60. Animals began operant self-administration of ethanol or saccharin after PND 85. After 10 weeks of daily operant self-administration, rats were tested in a progressive ratio paradigm. Two weeks later, self-administration was extinguished in all rats. Peri-adolescent ethanol consumption specifically enhanced the acquisition of ethanol self-administration, reduced the rate of extinction for ethanol self-administration, and quantitatively increased the reinforcing properties of ethanol during adulthood. Peri-adolescent saccharin consumption was without effect. The data indicate that ethanol consumption during peri-adolescence results in neuroadaptations that may specifically enhance the reinforcing properties of ethanol during adulthood. This increase in the reinforcing properties of ethanol could be a part of biological sequelae that are the basis for the effects of adolescent alcohol consumption on the increase in the rate of alcoholism during adulthood.
Keywords: Adolescence; Aging; alcoholism; Animals; Conditioning; Ethanol; Extinction; Female; Inbred Strains; Operant; Progressive ratio; Psychological; Rats; Reinforcement (Psychology); Reinforcement Schedule; Saccharin; Self Administration; self-administration

Repeated Binge Drinking Increases Perineuronal Nets in the Insular Cortex - Chen, Hu; He, Donghong; Lasek, Amy W. (Alcoholism, Clinical and Experimental Research, 2015)
BACKGROUND: Alcohol exposure leads to changes in the extracellular matrix (ECM) in the brain, which profoundly impacts neuronal plasticity. Perineuronal nets (PNs) are specialized ECM structures that enclose subpopulations of neurons in the cortex. Adolescent exposure to alcohol induces long-lasting increases in the expression of PN components in the cortex in adult mice. However, it has not been determined whether binge alcohol exposure in young adults alters PNs. Here, we examined PNs and their core components in the insula and primary motor cortex after repeated binge-like ethanol (EtOH) consumption in adult mice. METHODS: The 4-day drinking in the dark (DID) procedure was performed in mice for 1 or 6 weeks to model binge alcohol consumption. The impact of EtOH drinking on PNs was examined by fluorescent staining of brain sections using a marker for PNs, Wisteria floribunda agglutinin (WFA). In another set of experiments, cortex was dissected and Western blots and real-time quantitative polymerase chain reaction were performed to evaluate the expression of the PN proteins aggrecan, brevican, and phosphacan. RESULTS: Binge-like EtOH drinking for 6 weeks caused a significant increase in PNs in the insula, as measured by WFA binding. Aggrecan, brevican, and phosphacan protein expression, and aggrecan mRNA expression, were also elevated in the insula after 6 weeks of EtOH drinking. In contrast, expression of PN components did not change after 1 week of DID. The increase in PNs appears to be specific to the insula, because alterations were not observed in the primary motor cortex. CONCLUSIONS: Our results provide the first evidence that insular PNs increase after long-term binge drinking. The insula mediates compulsive alcohol use. As PNs influence neuronal firing and plasticity, increased PNs in the insula after multiple binge cycles may contribute to restricted neuronal plasticity and lead to the development of compulsive alcohol use.
Keywords: Aggrecans; Animals; Binge Drinking; Brevican; Cerebral Cortex; Chondroitin Sulfate Proteoglycans; Class 5; Ethanol; Extracellular Matrix; Insular Cortex; Male; Mice; Motor Cortex; Neurons; Perineuronal Nets; Receptor-Like Protein Tyrosine Phosphatases

Rewarding and aversive effects of ethanol in High Drinking in the Dark selectively bred mice - Barkley-Levenson, Amanda M.; Cunningham, Christopher L.; Smitasin, Phoebe J.; Crabbe, John C. (Addiction Biology, 2015)
Both rewarding and aversive effects contribute to alcohol consumption. Animals genetically predisposed to be high drinkers show reduced sensitivity to the aversive effects of alcohol, and in some instances, increased sensitivity to alcohol's rewarding effects. The present studies tested the high drinking in the dark (HDID) selected lines, a genetic model of drinking to intoxication, to determine whether intake in these mice was genetically related to sensitivity to alcohol aversion or reward. Male HDID mice from the first and second replicate lines (HDID-1 and HDID-2, respectively) and mice from the heterogeneous progenitor control population (HS/Npt, or HS) were conditioned for a taste aversion to a salt solution using two doses of alcohol, and lithium chloride (LiCl) and saline controls. In separate experiments, male and female HDID-1, HDID-2 and HS mice were conditioned for place preference using alcohol. HDID mice were found to have an attenuated sensitivity to alcohol at a moderate (2 g/kg) dose compared to HS mice, but did not differ on conditioned taste aversion to a high (4 g/kg) dose or LiCl or saline injections. HDID and HS mice showed comparable development of alcohol-induced conditioned place preference. These results indicate that high blood alcohol levels after drinking in the HDID mice is genetically related to attenuated aversion to alcohol, while sensitivity to alcohol reward is not altered in these mice. Thus, HDID mice may find a moderate dose of alcohol to be less aversive than control mice and consequently may drink more because of this reduced aversive sensitivity.
Keywords: alcohol; Alcohol Drinking; Animal; Animals; Behavior; Behavioral; Behavioral genetics; Binge Drinking; Central Nervous System Depressants; Classical; conditioned place preference; Conditioned taste aversion; Conditioning; Ethanol; Genetics; Inbred Strains; Mice; Punishment; Reward; selected lines

Role of interleukin-1 receptor signaling in the behavioral effects of ethanol and benzodiazepines - Blednov, Yuri A.; Benavidez, Jillian M.; Black, Mendy; Mayfield, Jody; Harris, R. Adron (Neuropharmacology, 2015)
Gene expression studies identified the interleukin-1 receptor type I (IL-1R1) as part of a pathway associated with a genetic predisposition to high alcohol consumption, and lack of the endogenous IL-1 receptor antagonist (IL-1ra) strongly reduced ethanol intake in mice. Here, we compared ethanol-mediated behaviors in mice lacking Il1rn or Il1r1. Deletion of Il1rn (the gene encoding IL-1ra) increases sensitivity to the sedative/hypnotic effects of ethanol and flurazepam and reduces severity of acute ethanol withdrawal. Conversely, deletion of Il1r1 (the gene encoding the IL-1 receptor type I, IL-1R1) reduces sensitivity to the sedative effects of ethanol and flurazepam and increases the severity of acute ethanol withdrawal. The sedative effects of ketamine and pentobarbital were not altered in the knockout (KO) strains. Ethanol intake and preference were not changed in mice lacking Il1r1 in three different tests of ethanol consumption. Recovery from ethanol-induced motor incoordination was only altered in female mice lacking Il1r1. Mice lacking Il1rn (but not Il1r1) showed increased ethanol clearance and decreased ethanol-induced conditioned taste aversion. The increased ethanol- and flurazepam-induced sedation in Il1rn KO mice was decreased by administration of IL-1ra (Kineret), and pre-treatment with Kineret also restored the severity of acute ethanol withdrawal. Ethanol-induced sedation and withdrawal severity were changed in opposite directions in the null mutants, indicating that these responses are likely regulated by IL-1R1 signaling, whereas ethanol intake and preference do not appear to be solely regulated by this pathway.
Keywords: 129 Strain; Alcohol Drinking; Alcohol withdrawal; Anakinra; Animal; Animals; Avoidance Learning; Behavior; Benzodiazepines; Conditioned taste aversion; Drinking in the dark; Ethanol; Female; Flurazepam; Hypnotics and Sedatives; IL-1R1; IL-1ra; Il1r1; Il1rn; Inbred C57BL; Interleukin 1 Receptor Antagonist Protein; Interleukin-1 Type I; Ketamine; Kineret; Knockout; Knockout mice; Loss of Righting Reflex; Male; Mice; Motor Activity; Pentobarbital; Receptors; Severity of Illness Index; Substance Withdrawal Syndrome; Taste Perception; Two-bottle choice

Role of the IL-1 receptor antagonist in ethanol-induced regulation of GABAergic transmission in the central amygdala - Bajo, M.; Herman, M. A.; Varodayan, F. P.; Oleata, C. S.; Madamba, S. G.; Harris, R. A.; Blednov, Y. A.; Roberto, M. (Brain, Behavior, and Immunity, 2015)
The IL-1 receptor antagonist (IL-1ra), encoded by the Il1rn gene, is an endogenous antagonist of the IL-1 receptor. Studies of Il1rn knockout (KO) and wild type (WT) mice identified differences in several ethanol-related behaviors, some of which may be mediated by GABAergic transmission in the central nucleus of the amygdala (CeA). In this study we examined phasic (both evoked and spontaneous) and tonic GABAergic transmission in the CeA of Il1rn KO and WT mice and the ethanol sensitivity of these GABAergic synapses. The mean amplitude of baseline evoked GABAA-inhibitory postsynaptic potentials (IPSPs), and the baseline frequency of spontaneous GABAA-inhibitory postsynaptic currents (sIPSCs), but not the frequency of miniature GABAA-IPSCs (mIPSCs), were significantly increased in KO compared to WT mice, indicating enhanced presynaptic action potential-dependent GABA release in the CeA of KO mice. In KO mice, we also found a cell-type specific switch in the ongoing tonic GABAA receptor conductance such that the tonic conductance in low threshold bursting (LTB) neurons is lost and a tonic conductance in late spiking (LS) neurons appears. Notably, the ethanol-induced facilitation of evoked and spontaneous GABA release was lost in most of the CeA neurons from KO compared to WT mice. Ethanol superfusion increased the sIPSC rise and decay times in both KO and WT mice, suggesting ethanol-induced postsynaptic effects. The pretreatment of CeA slices with exogenous IL-1ra (Kineret; 100ng/ml) returned sIPSC frequency in KO mice to the levels found in WT. Importantly, Kineret also restored ethanol-induced potentiation of the sIPSC frequency in the KO mice. These results show that IL-1ra regulates baseline GABAergic transmission in the CeA and is critical for the ethanol effects at these synapses.
Keywords: Amygdala; Animals; CeA; Central Nervous System Depressants; Ethanol; GABA(A); GABA-A; GABAergic Neurons; gamma-Aminobutyric Acid; Il1rn knockout mice; Inhibitory Postsynaptic Potentials; Interleukin 1 Receptor Antagonist Protein; IPSCs; Kineret; Knockout; Mice; Patch-Clamp Techniques; Receptors

A Selective Role for Lmo4 in Cue-Reward Learning - Maiya, Rajani; Mangieri, Regina A.; Morrisett, Richard A.; Heberlein, Ulrike; Messing, Robert O. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2015)
The ability to use environmental cues to predict rewarding events is essential to survival. The basolateral amygdala (BLA) plays a central role in such forms of associative learning. Aberrant cue-reward learning is thought to underlie many psychopathologies, including addiction, so understanding the underlying molecular mechanisms can inform strategies for intervention. The transcriptional regulator LIM-only 4 (LMO4) is highly expressed in pyramidal neurons of the BLA, where it plays an important role in fear learning. Because the BLA also contributes to cue-reward learning, we investigated the role of BLA LMO4 in this process using Lmo4-deficient mice and RNA interference. Lmo4-deficient mice showed a selective deficit in conditioned reinforcement. Knockdown of LMO4 in the BLA, but not in the nucleus accumbens, recapitulated this deficit in wild-type mice. Molecular and electrophysiological studies identified a deficit in dopamine D2 receptor signaling in the BLA of Lmo4-deficient mice. These results reveal a novel, LMO4-dependent transcriptional program within the BLA that is essential to cue-reward learning.
Keywords: Adaptor Proteins; Animals; Association Learning; basolateral amygdala; Basolateral Nuclear Complex; Choice Behavior; conditioned reinforcement; Conditioning; Cues; Dopamine D2; Green Fluorescent Proteins; In Vitro Techniques; Inbred C57BL; LIM Domain Proteins; Mice; Motivation; Neurons; Operant; Patch-Clamp Techniques; Proto-Oncogene Proteins c-akt; Receptors; Reward; RNA; Signal Transducing; Small Interfering; Sucrose; Transcription; Transgenic

The sequenced rat brain transcriptome–its use in identifying networks predisposing alcohol consumption - Saba, Laura M.; Flink, Stephen C.; Vanderlinden, Lauren A.; Israel, Yedy; Tampier, Lutske; Colombo, Giancarlo; Kiianmaa, Kalervo; Bell, Richard L.; Printz, Morton P.; Flodman, Pamela; Koob, George; Richardson, Heather N.; et al. (The FEBS journal, 2015)
A quantitative genetic approach, which involves correlation of transcriptional networks with the phenotype in a recombinant inbred (RI) population and in selectively bred lines of rats, and determination of coinciding quantitative trait loci for gene expression and the trait of interest, has been applied in the present study. In this analysis, a novel approach was used that combined DNA-Seq data, data from brain exon array analysis of HXB/BXH RI rat strains and six pairs of rat lines selectively bred for high and low alcohol preference, and RNA-Seq data (including rat brain transcriptome reconstruction) to quantify transcript expression levels, generate co-expression modules and identify biological functions that contribute to the predisposition of consuming varying amounts of alcohol. A gene co-expression module was identified in the RI rat strains that contained both annotated and unannotated transcripts expressed in the brain, and was associated with alcohol consumption in the RI panel. This module was found to be enriched with differentially expressed genes from the selected lines of rats. The candidate genes within the module and differentially expressed genes between high and low drinking selected lines were associated with glia (microglia and astrocytes) and could be categorized as being related to immune function, energy metabolism and calcium homeostasis, as well as glial-neuronal communication. The results of the present study show that there are multiple combinations of genetic factors that can produce the same phenotypic outcome. Although no single gene accounts for predisposition to a particular level of alcohol consumption in every animal model, coordinated differential expression of subsets of genes in the identified pathways produce similar phenotypic outcomes. DATABASE: The datasets supporting the results of the present study are available at http://phenogen.ucdenver.edu.
Keywords: Alcohol consumption; Alcohol Drinking; Animals; Brain; Databases; Gene Expression; Gene Regulatory Networks; Genetic; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; HXB RI rat strains; Inbred BN; Inbred Strains; Male; Neuroinflammation; Nucleic Acid; rat selected lines; Rats; Recombination; Transcriptome; Wistar

Splicing landscape of the eight collaborative cross founder strains - Zheng, Christina L.; Wilmot, Beth; Walter, Nicole AR; Oberbeck, Denesa; Kawane, Sunita; Searles, Robert P.; McWeeney, Shannon K.; Hitzemann, Robert (BMC genomics, 2015)
BACKGROUND: The Collaborative Cross (CC) is a large panel of genetically diverse recombinant inbred mouse strains specifically designed to provide a systems genetics resource for the study of complex traits. In part, the utility of the CC stems from the extensive genome-wide annotations of founder strain sequence and structural variation. Still missing, however, are transcriptome-specific annotations of the CC founder strains that could further enhance the utility of this resource. RESULTS: We provide a comprehensive survey of the splicing landscape of the 8 CC founder strains by leveraging the high level of alternative splicing within the brain. Using deep transcriptome sequencing, we found that a majority of the splicing landscape is conserved among the 8 strains, with ~65% of junctions being shared by at least 2 strains. We, however, found a large number of potential strain-specific splicing events as well, with an average of ~3000 and ~500 with ≥3 and ≥10 sequence read coverage, respectively, within each strain. To better understand strain-specific splicing within the CC founder strains, we defined criteria for and identified high-confidence strain-specific splicing events. These splicing events were defined as exon-exon junctions 1) found within only one strain, 2) with a read coverage ≥10, and 3) defined by a canonical splice site. With these criteria, a total of 1509 high-confidence strain-specific splicing events were identified, with the majority found within two of the wild-derived strains, CAST and PWK. Strikingly, the overwhelming majority, 94%, of these strain-specific splicing events are not yet annotated. Strain-specific splicing was also located within genomic regions recently reported to be over- and under-represented within CC populations. CONCLUSIONS: Phenotypic characterization of CC populations is increasing; thus these results will not only aid in further elucidating the transcriptomic architecture of the individual CC founder strains, but they will also help in guiding the utilization of the CC populations in the study of complex traits. This report is also the first to establish guidelines in defining and identifying strain-specific splicing across different mouse strains.
Keywords: Animals; Genome; Inbred Strains; Mice; Molecular Sequence Annotation; Quantitative Trait Loci; RNA Splicing; Transcriptome

The stress response neuropeptide CRF increases amyloid-β production by regulating γ-secretase activity - Park, Hyo-Jin; Ran, Yong; Jung, Joo In; Holmes, Oliver; Price, Ashleigh R.; Smithson, Lisa; Ceballos-Diaz, Carolina; Han, Chul; Wolfe, Michael S.; Daaka, Yehia; Ryabinin, Andrey E.; Kim, Seong-Hun; et al. (The EMBO journal, 2015)
The biological underpinnings linking stress to Alzheimer's disease (AD) risk are poorly understood. We investigated how corticotrophin releasing factor (CRF), a critical stress response mediator, influences amyloid-β (Aβ) production. In cells, CRF treatment increases Aβ production and triggers CRF receptor 1 (CRFR1) and γ-secretase internalization. Co-immunoprecipitation studies establish that γ-secretase associates with CRFR1; this is mediated by β-arrestin binding motifs. Additionally, CRFR1 and γ-secretase co-localize in lipid raft fractions, with increased γ-secretase accumulation upon CRF treatment. CRF treatment also increases γ-secretase activity in vitro, revealing a second, receptor-independent mechanism of action. CRF is the first endogenous neuropeptide that can be shown to directly modulate γ-secretase activity. Unexpectedly, CRFR1 antagonists also increased Aβ. These data collectively link CRF to increased Aβ through γ-secretase and provide mechanistic insight into how stress may increase AD risk. They also suggest that direct targeting of CRF might be necessary to effectively modulate this pathway for therapeutic benefit in AD, as CRFR1 antagonists increase Aβ and in some cases preferentially increase Aβ42 via complex effects on γ-secretase.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; amyloid‐β; Analysis of Variance; Animals; Biological; Blotting; corticotrophin releasing factor; Corticotropin-Releasing Hormone; Cyclic AMP; Enzyme-Linked Immunosorbent Assay; Fluorescence; HEK293 Cells; Humans; Hypothalamo-Hypophyseal System; Immunoprecipitation; Inbred C57BL; Membrane Microdomains; Mice; Microscopy; Models; Physiological; Pituitary-Adrenal System; Real-Time Polymerase Chain Reaction; Receptors; Stress; Western; β‐arrestin; γ‐secretase

The synaptoneurosome transcriptome: a model for profiling the emolecular effects of alcohol - Most, D.; Ferguson, L.; Blednov, Y.; Mayfield, R. D.; Harris, R. A. (The Pharmacogenomics Journal, 2015)
Chronic alcohol consumption changes gene expression, likely causing persistent remodeling of synaptic structures via altered translation of mRNAs within synaptic compartments of the cell. We profiled the transcriptome from synaptoneurosomes (SNs) and paired total homogenates (THs) from mouse amygdala following chronic voluntary alcohol consumption. In SN, both the number of alcohol-responsive mRNAs and the magnitude of fold-change were greater than in THs, including many GABA-related mRNAs upregulated in SNs. Furthermore, SN gene co-expression analysis revealed a highly connected network, demonstrating coordinated patterns of gene expression and highlighting alcohol-responsive biological pathways, such as long-term potentiation, long-term depression, glutamate signaling, RNA processing and upregulation of alcohol-responsive genes within neuroimmune modules. Alterations in these pathways have also been observed in the amygdala of human alcoholics. SNs offer an ideal model for detecting intricate networks of coordinated synaptic gene expression and may provide a unique system for investigating therapeutic targets for the treatment of alcoholism.
Keywords: Alcohol Drinking; alcoholism; Amygdala; Animals; Ethanol; Female; gamma-Aminobutyric Acid; Gene Expression; Gene Expression Profiling; Gene Regulatory Networks; Humans; Inbred C57BL; Messenger; Mice; RNA; Signal Transduction; Transcriptome

Targeting glutamate uptake to treat alcohol use disorders - Rao, P. S. S.; Bell, Richard L.; Engleman, Eric A.; Sari, Youssef (Frontiers in Neuroscience, 2015)
Alcoholism is a serious public health concern that is characterized by the development of tolerance to alcohol's effects, increased consumption, loss of control over drinking and the development of physical dependence. This cycle is often times punctuated by periods of abstinence, craving and relapse. The development of tolerance and the expression of withdrawal effects, which manifest as dependence, have been to a great extent attributed to neuroadaptations within the mesocorticolimbic and extended amygdala systems. Alcohol affects various neurotransmitter systems in the brain including the adrenergic, cholinergic, dopaminergic, GABAergic, glutamatergic, peptidergic, and serotonergic systems. Due to the myriad of neurotransmitter and neuromodulator systems affected by alcohol, the efficacies of current pharmacotherapies targeting alcohol dependence are limited. Importantly, research findings of changes in glutamatergic neurotransmission induced by alcohol self- or experimenter-administration have resulted in a focus on therapies targeting glutamatergic receptors and normalization of glutamatergic neurotransmission. Glutamatergic receptors implicated in the effects of ethanol include the ionotropic glutamate receptors (AMPA, Kainate, and NMDA) and some metabotropic glutamate receptors. Regarding glutamatergic homeostasis, ceftriaxone, MS-153, and GPI-1046, which upregulate glutamate transporter 1 (GLT1) expression in mesocorticolimbic brain regions, reduce alcohol intake in genetic animal models of alcoholism. Given the hyperglutamatergic/hyperexcitable state of the central nervous system induced by chronic alcohol abuse and withdrawal, the evidence thus far indicates that a restoration of glutamatergic concentrations and activity within the mesocorticolimbic system and extended amygdala as well as multiple memory systems holds great promise for the treatment of alcohol dependence.
Keywords: alcohol; dopamine; EAAT2; GLT1; glutamate; Neurotransmitter

Transcriptome organization for chronic alcohol abuse in human brain - Farris, S. P.; Arasappan, D.; Hunicke-Smith, S.; Harris, R. A.; Mayfield, R. D. (Molecular Psychiatry, 2015)
Alcohol dependence is a heterogeneous psychiatric disorder characterized by high genetic heritability and neuroadaptations occurring from repeated drug exposure. Through an integrated systems approach we observed consistent differences in transcriptome organization within postmortem human brain tissue associated with the lifetime consumption of alcohol. Molecular networks, determined using high-throughput RNA sequencing, for drinking behavior were dominated by neurophysiological targets and signaling mechanisms of alcohol. The systematic structure of gene sets demonstrates a novel alliance of multiple ion channels, and related processes, underlying lifetime alcohol consumption. Coordinate expression of these transcripts was enriched for genome-wide association signals in alcohol dependence and a meta-analysis of alcohol self-administration in mice. Further dissection of genes within alcohol consumption networks revealed the potential interaction of alternatively spliced transcripts. For example, expression of a human-specific isoform of the voltage-gated sodium channel subunit SCN4B was significantly correlated to lifetime alcohol consumption. Overall, our work demonstrates novel convergent evidence for biological networks related to excessive alcohol consumption, which may prove fundamentally important in the development of pharmacotherapies for alcohol dependence.
Keywords: Alcohol Drinking; alcoholism; Animals; Brain; Chronic Disease; Computational Biology; Gene Expression Profiling; Gene Regulatory Networks; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Mice; Postmortem Changes; Transcriptome; Voltage-Gated Sodium Channel beta-4 Subunit

15 years of genetic approaches in vivo for addiction research: opioid receptor and peptide gene knockout in mouse models of drug abuse - Charbogne, Pauline; Kieffer, Brigitte L.; Befort, Katia (Neuropharmacology, 2014)
The endogenous opioid system is expressed throughout the brain reinforcement circuitry, and plays a major role in reward processing, mood control and the development of addiction. This neuromodulator system is composed of three receptors, mu, delta and kappa, interacting with a family of opioid peptides derived from POMC (β-endorphin), preproenkephalin (pEnk) and preprodynorphin (pDyn) precursors. Knockout mice targeting each gene of the opioid system have been created almost two decades ago. Extending classical pharmacology, these mutant mice represent unique tools to tease apart the specific role of each opioid receptor and peptide in vivo, and a powerful approach to understand how the opioid system modulates behavioral effects of drugs of abuse. The present review summarizes these studies, with a focus on major drugs of abuse including morphine/heroin, cannabinoids, psychostimulants, nicotine or alcohol. Genetic data, altogether, set the mu receptor as the primary target for morphine and heroin. In addition, this receptor is essential to mediate rewarding properties of non-opioid drugs of abuse, with a demonstrated implication of β-endorphin for cocaine and nicotine. Delta receptor activity reduces levels of anxiety and depressive-like behaviors, and facilitates morphine-context association. PEnk is involved in these processes and delta/pEnk signaling likely regulates alcohol intake. The kappa receptor mainly interacts with pDyn peptides to limit drug reward, and mediate dysphoric effects of cannabinoids and nicotine. Kappa/dynorphin activity also increases sensitivity to cocaine reward under stressful conditions. The opioid system remains a prime candidate to develop successful therapies in addicted individuals, and understanding opioid-mediated processes at systems level, through emerging genetic and imaging technologies, represents the next challenging goal and a promising avenue in addiction research.

The 5-HT7 receptor as a potential target for treating drug and alcohol abuse - Hauser, Sheketha R.; Hedlund, Peter B.; Roberts, Amanda J.; Sari, Youssef; Bell, Richard L.; Engleman, Eric A. (Frontiers in Neuroscience, 2014)
Alcohol and drug abuse take a large toll on society and affected individuals. However, very few effective treatments are currently available to treat alcohol and drug addiction. Basic and clinical research has begun to provide some insights into the underlying neurobiological systems involved in the addiction process. Several neurotransmitter pathways have been implicated and distinct reward neurocircuitry have been proposed-including the mesocorticolimbic dopamine (MCL-DA) system and the extended amygdala. The serotonin (5-HT) neurotransmitter system is of particular interest and multiple 5-HT receptors are thought to play significant roles in alcohol and drug self-administration and the development of drug dependence. Among the 5-HT receptors, the 5-HT7 receptor is currently undergoing characterization as a potential target for the treatment of several psychiatric disorders. Although this receptor has received only limited research regarding addictive behaviors, aspects of its neuroanatomical, biochemical, physiological, pharmacological, and behavioral profiles suggest that it could play a key role in the addiction process. For instance, genomic studies in humans have suggested a link between variants in the gene encoding the 5-HT7 receptor and alcoholism. Recent behavioral testing using high-affinity antagonists in mice and preliminary tests with alcohol-preferring rats suggest that this receptor could mediate alcohol consumption and/or reinforcement and play a role in seeking/craving behavior. Interest in the development of new and more selective pharmacological agents for this receptor will aid in examining the 5-HT7 receptor as a novel target for treating addiction.
Keywords: alcohol abuse; drug abuse; Genetics; mesocorticolimbic dopamine system; Pharmacogenetics; Selective breeding; serotonin-7 (5-HT7)

Alcohol dependence: molecular and behavioral evidence - Trudell, James R.; Messing, Robert O.; Mayfield, Jody; Harris, R. Adron (Trends in Pharmacological Sciences, 2014)
Alcohol dependence is a complex condition with clear genetic factors. Some of the leading candidate genes code for subunits of the inhibitory GABAA and glycine receptors. These and related ion channels are also targets for the acute actions of alcohol, and there is considerable progress in understanding interactions of alcohol with these proteins at the molecular and even atomic levels. X-ray structures of open and closed states of ion channels combined with structural modeling and site-directed mutagenesis have elucidated direct actions of alcohol. Alcohol also alters channel function by translational and post-translational mechanisms, including phosphorylation and protein trafficking. Construction of mutant mice with either deletion of key proteins or introduction of alcohol-resistant channels has further linked specific proteins with discrete behavioral effects of alcohol. A combination of approaches, including genome wide association studies in humans, continues to advance the molecular basis of alcohol action on receptor structure and function.
Keywords: alcoholism; Animals; Behavior; chronic alcohol consumption; crystal structures; Ethanol; GABA(A); Gene Expression; GLIC; Glycine; Humans; Ion Channels; knockin mice; Knockout; LGICs; Mice; NMDA; PKC; trafficking

Is the alcohol deprivation effect genetically mediated? Studies with HXB/BXH recombinant inbred rat strains - Vanderlinden, Lauren A.; Saba, Laura M.; Printz, Morton P.; Flodman, Pamela; Koob, George; Richardson, Heather N.; Hoffman, Paula L.; Tabakoff, Boris (Alcoholism, Clinical and Experimental Research, 2014)
BACKGROUND: Two features of alcohol addiction that have been widely studied in animal models are relapse drinking following periods of alcohol abstinence and the escalation of alcohol consumption after chronic continuous or intermittent alcohol exposure. The genetic contribution to these phenotypes has not been systematically investigated. METHODS: HXB/BXH recombinant inbred (RI) rat strains were given access to alcohol sequentially as follows: alcohol (10%) as the only fluid for 1 week; alcohol (10%) and water in a 2-bottle choice paradigm for 7 weeks ("pre-alcohol deprivation effect [ADE] alcohol consumption"); 2 weeks of access to water only (alcohol deprivation); and 2 weeks of reaccess to 10% alcohol and water ("post-ADE alcohol consumption"). The periods of deprivation and reaccess to alcohol were repeated 3 times. The ADE was defined as the amount of alcohol consumed in the first 24 hours after deprivation minus the average daily amount of alcohol consumed in the week prior to deprivation. Heritability of the phenotypes was determined by analysis of variance, and quantitative trait loci (QTLs) were identified. RESULTS: All strains showed increased alcohol consumption, compared to the predeprivation period, in the first 24 hours after each deprivation (ADE). Broad-sense heritability of the ADEs was low (ADE1, 9.1%; ADE2, 26.2%; ADE3, 16.3%). Alcohol consumption levels were relatively stable over weeks 2 to 7. Post-ADE alcohol consumption levels consistently increased in some strains and were decreased or unchanged in others. Heritability of pre- and post-ADE alcohol consumption was high and increased over time (week 2, 38.5%; week 7, 51.1%; week 11, 56.8%; week 15, 63.3%). QTLs for pre- and post-ADE alcohol consumption were similar, but the strength of the QTL association with the phenotype decreased over time. CONCLUSIONS: In the HXB/BXH RI rat strains, genotypic variance does not account for a large proportion of phenotypic variance in the ADE phenotype (low heritability), suggesting a role of environmental factors. In contrast, a large proportion of the variance across the RI strains in pre- and post-ADE alcohol consumption is due to genetically determined variance (high heritability).
Keywords: Addictive; Alcohol consumption; Alcohol Deprivation Effect; Alcohol Drinking; alcoholism; Animals; Behavior; Choice Behavior; Genotype; Heritability; Heritable; HXB/BXH Recombinant Inbred Rat Strains; Inbred Strains; Male; Phenotype; Quantitative Trait; Quantitative Trait Loci; Rats; Species Specificity

Altered gamma-aminobutyric acid type B receptor subunit 1 splicing in alcoholics - Lee, Changhoon; Mayfield, R. Dayne; Harris, R. Adron (Biological Psychiatry, 2014)
BACKGROUND: Chronic alcohol exposure can change splice variant expression. The gamma-aminobutyric acid type B (GABAB) receptor undergoes splicing and is an alcoholism treatment target, but there is little information about splicing changes in this receptor in alcoholics. We studied GABAB receptor subunit 1 (GABAB1) splicing in alcoholic postmortem brains. METHODS: To maximize GABAB1 splice junction identification, we combined gene specific libraries with RNA-seq. Splice junctions and mapped reads were also found from intronic and intergenic regions. We compared GABAB1 splice junctions in prefrontal cortices from 14 alcoholic and 15 control subjects and introduced new strategies, reads per kilobase of splice junction model per million mapped reads and reads per kilobase of gene model per million mapped reads, for quantitating splice junction and gene expression. RESULTS: Novel splice junction detection indicated that the GABAB1 gene is at least two times longer than the previously reported gene length. GABAB1 exon and intron expression data showed low expression at the 5' end exons and exon grouping. This indicated that there are short splicing variants in addition to GABAB receptor subunit GABAB1a, the longest known major transcript. We found that chronic alcohol altered exon/intron expression and splice junction levels. Decreased expression of the gamma-aminobutyric acid binding site, a transmembrane domain and a microRNA binding site may decrease normal GABAB1 transcript population and thereby decrease normal signal transduction in alcoholics. CONCLUSIONS: We discovered novel, complex splicing of GABAB1 in human brain and showed that chronic alcohol produces additional splicing complexity.
Keywords: Adult; Aged; alcoholism; Brain; exon/intron expression; Female; GABA-B; GABAB receptor; human prefrontal cortex; Humans; Male; Middle Aged; Protein Isoforms; Protein Subunits; Receptors; RNA Splicing; RNA-seq; splice junction

Associations between in vivo neuroimaging and postmortem brain cytokine markers in a rodent model of Wernicke's encephalopathy - Zahr, Natalie M.; Alt, Carsten; Mayer, Dirk; Rohlfing, Torsten; Manning-Bog, Amy; Luong, Richard; Sullivan, Edith V.; Pfefferbaum, Adolf (Experimental Neurology, 2014)
{Thiamine (vitamin B1) deficiency, associated with a variety of conditions, including chronic alcoholism and bariatric surgery for morbid obesity, can result in the neurological disorder Wernicke's encephalopathy (WE). Recent work building upon early observations in animal models of thiamine deficiency has demonstrated an inflammatory component to the neuropathology observed in thiamine deficiency. The present, multilevel study including in vivo magnetic resonance imaging (MRI) and spectroscopy (MRS) and postmortem quantification of chemokine and cytokine proteins sought to determine whether a combination of these in vivo neuroimaging tools could be used to characterize an in vivo MR signature for neuroinflammation. Thiamine deficiency for 12days was used to model neuroinflammation; glucose loading in thiamine deficiency was used to accelerate neurodegeneration. Among 38 animals with regional brain tissue assayed postmortem for cytokine/chemokine protein levels, three groups of rats (controls+glucose
Keywords: Analysis of Variance; Animal; Animals; Aspartic Acid; Brain; Creatine; Cytokines; Disease Models; Immunohistochemistry; Lactate; Liver; Magnetic Resonance Imaging; Magnetic Resonance Spectroscopy; Male; MCP-1; Microglia; Neurologic Examination; Rats; TDP; Thiamine; Time Factors; Wernicke Encephalopathy; Wistar

Bioinformatics analyses reveal age-specific neuroimmune modulation as a target for treatment of high ethanol drinking - Agrawal, Rajiv G.; Owen, Julie A.; Levin, Patricia S.; Hewetson, Aveline; Berman, Ari E.; Franklin, Scott R.; Hogue, Ryan J.; Chen, Yukun; Walz, Chris; Colvard, Benjamin D.; Nguyen, Jonathan; Velasquez, Oscar; et al. (Alcoholism, Clinical and Experimental Research, 2014)
BACKGROUND: Use of in silico bioinformatics analyses has led to important leads in the complex nature of alcoholism at the genomic, epigenomic, and proteomic level, but has not previously been successfully translated to the development of effective pharmacotherapies. In this study, a bioinformatics approach led to the discovery of neuroimmune pathways as an age-specific druggable target. Minocycline, a neuroimmune modulator, reduced high ethanol (EtOH) drinking in adult, but not adolescent, mice as predicted a priori. METHODS: Age and sex-divergent effects in alcohol consumption were quantified in FVB/NJ × C57BL/6J F1 mice given access to 20% alcohol using a 4 h/d, 4-day drinking-in-dark (DID) paradigm. In silico bioinformatics pathway overrepresentation analysis for age-specific effects of alcohol in brain was performed using gene expression data collected in control and DID-treated, adolescent and adult, male mice. Minocycline (50 mg/kg i.p., once daily) or saline alone was tested for an effect on EtOH intake in the F1 and C57BL/6J (B6) mice across both age and gender groups. Effects of minocycline on the pharmacokinetic properties of alcohol were evaluated by comparing the rates of EtOH elimination between the saline- and minocycline-treated F1 and B6 mice. RESULTS: Age and gender differences in DID consumption were identified. Only males showed a clear developmental increase difference in drinking over time. In silico analyses revealed neuroimmune-related pathways as significantly overrepresented in adult, but not in adolescent, male mice. As predicted, minocycline treatment reduced drinking in adult, but not adolescent, mice. The age effect was present for both genders, and in both the F1 and B6 mice. Minocycline had no effect on the pharmacokinetic elimination of EtOH. CONCLUSIONS: Our results are a proof of concept that bioinformatics analysis of brain gene expression can lead to the generation of new hypotheses and a positive translational outcome for individualized pharmacotherapeutic treatment of high alcohol consumption.
Keywords: Aging; alcoholism; Animals; Anti-Bacterial Agents; Bioinformatics; Central Nervous System Depressants; Computational Biology; Drinking-in-Dark; Ethanol; Female; FVB/NJ × C57BL/6J F1 Mouse; Inbred C57BL; Male; Medications Development; Mice; Minocycline; Neuroimmunomodulation; Sex Characteristics

CCL2-ethanol interactions and hippocampal synaptic protein expression in a transgenic mouse model - Gruol, Donna L.; Vo, Khanh; Bray, Jennifer G.; Roberts, Amanda J. (Frontiers in Integrative Neuroscience, 2014)
Chronic exposure to ethanol produces a number of detrimental effects on behavior. Neuroadaptive changes in brain structure or function underlie these behavioral effects and may be transient or persistent in nature. Central to the functional changes are alterations in the biology of neuronal and glial cells of the brain. Recent data show that ethanol induces glial cells of the brain to produce elevated levels of neuroimmune factors including CCL2, a key innate immune chemokine. Depending on the conditions of ethanol exposure, the upregulated levels of CCL2 can be transient or persistent and outlast the period of ethanol exposure. Importantly, results indicate that the upregulated levels of CCL2 may lead to CCL2-ethanol interactions that mediate or regulate the effects of ethanol on the brain. Glial cells are in close association with neurons and regulate many neuronal functions. Therefore, effects of ethanol on glial cells may underlie some of the effects of ethanol on neurons. To investigate this possibility, we are studying effects of chronic ethanol on hippocampal synaptic function in a transgenic mouse model that expresses elevated levels of CCL2 in the brain through enhanced glial expression, a situation know to occur in alcoholics. Both CCL2 and ethanol have been reported to alter synaptic function in the hippocampus. In the current study, we determined if interactions are evident between CCL2 and ethanol at the level of hippocampal synaptic proteins. Two ethanol exposure paradigms were used; the first involved ethanol exposure by drinking and the second involved ethanol exposure in a paradigm that combines drinking plus ethanol vapor. The first paradigm does not produce dependence on ethanol, whereas the second paradigm is commonly used to produce ethanol dependence. Results show modest effects of both ethanol exposure paradigms on the level of synaptic proteins in the hippocampus of CCL2 transgenic mice compared with their non-transgenic littermate controls, consistent with ethanol-CCL2 interactions. No evidence of toxic effects of CCL2 or CCL2-ethanol interactions was observed. Taken together, these results support the idea that ethanol induced astrocyte production of CCL2 can result in neuroadaptive changes that interact with the actions of ethanol.
Keywords: alcohol use disorders; astrocyte; Chemokine; chronic treatment; Neuroimmune; Western blot

Cell type-specific synaptic encoding of ethanol exposure in the nucleus accumbens shell - Jeanes, Z. M.; Buske, T. R.; Morrisett, R. A. (Neuroscience, 2014)
Synaptic alterations in the nucleus accumbens (NAc) are crucial for the aberrant reward-associated learning that forms the foundation of drug dependence. Altered glutamatergic synaptic plasticity, in particular, is thought to be a vital component of the neurobiological underpinnings of addictive behavior. The development of bacterial artificial chromosome-eGFP (enhanced green fluorescent protein) transgenic mice that express eGFP driven by endogenous D1 dopamine receptor (D1R) promoters has now allowed investigation of the cell type-specific synaptic modifications in the NAc in response to drugs of abuse. In this study, we used whole-cell ex vivo slice electrophysiology in Drd1-eGFP mice to investigate cell type-specific alterations in NAc synaptic plasticity following ethanol exposure. Electrophysiological recordings were made from eGFP-expressing medium spiny neurons (D1+ MSNs) and non-eGFP-expressing (putative D2 receptor-expressing) (D1- MSNs) from the shell subregion of the NAc. We observed low frequency-induced long-term depression (1Hz-LTD) of α-amino-3-hydroxy-5-methyl-isoxazole-4-propionic acid (AMPA)-mediated excitatory postsynaptic currents (EPSCs) solely in D1+ MSNs. However, 24h following four consecutive days of in vivo chronic intermittent ethanol (CIE) vapor exposure, 1-Hz LTD was conversely observed only in D1- MSNs, and now absent in D1+ MSNs. Complete recovery of the baseline plasticity phenotype in both cell types required a full 2 weeks of withdrawal from CIE vapor exposure. Thus, we observed a cell type specificity of synaptic plasticity in the NAc shell, as well as, a gradual recovery of the pre-ethanol exposure plasticity state following extended withdrawal. These changes highlight the adaptability of NAc shell MSNs to the effects of ethanol exposure and may represent critical neuroadaptations underlying the development of ethanol dependence.
Keywords: alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; Animals; Central Nervous System Depressants; Dopamine D1; drug dependence; Ethanol; Excitatory Postsynaptic Potentials; GABAergic Neurons; Green Fluorescent Proteins; Inbred C57BL; long-term depression; Long-Term Synaptic Depression; Male; mesocorticolimbic; metaplasticity; Mice; neuroadaptation; Neuronal Plasticity; Nucleus Accumbens; Patch-Clamp Techniques; Receptors; synaptic plasticity; Tissue Culture Techniques; Transgenic

Changes in gene expression within the extended amygdala following binge-like alcohol drinking by adolescent alcohol-preferring (P) rats - McBride, William J.; Kimpel, Mark W.; McClintick, Jeanette N.; Ding, Zheng-Ming; Edenberg, Howard J.; Liang, Tiebing; Rodd, Zachary A.; Bell, Richard L. (Pharmacology, Biochemistry, and Behavior, 2014)
The objective of this study was to determine changes in gene expression within the extended amygdala following binge-like alcohol drinking by male adolescent alcohol-preferring (P) rats. Starting at 28 days of age, P rats were given concurrent access to 15 and 30% ethanol for 3 one-h sessions/day for 5 consecutive days/week for 3 weeks. Rats were killed by decapitation 3 h after the first ethanol access session on the 15th day of drinking. RNA was prepared from micropunch samples of the nucleus accumbens shell (Acb-sh) and central nucleus of the amygdala (CeA). Ethanol intakes were 2.5-3.0 g/kg/session. There were 154 and 182 unique named genes that significantly differed (FDR=0.2) between the water and ethanol group in the Acb-sh and CeA, respectively. Gene Ontology (GO) analyses indicated that adolescent binge drinking produced changes in biological processes involved with cell proliferation and regulation of cellular structure in the Acb-sh, and in neuron projection and positive regulation of cellular organization in the CeA. Ingenuity Pathway Analysis indicated that, in the Acb-sh, there were several major intracellular signaling pathways (e.g., cAMP-mediated and protein kinase A signaling pathways) altered by adolescent drinking, with 3-fold more genes up-regulated than down-regulated in the alcohol group. The cAMP-mediated signaling system was also up-regulated in the CeA of the alcohol group. Weighted gene co-expression network analysis indicated significant G-protein coupled receptor signaling and transmembrane receptor protein kinase signaling categories in the Acb-sh and CeA, respectively. Overall, the results of this study indicated that binge-like alcohol drinking by adolescent P rats is differentially altering the expression of genes in the Acb-sh and CeA, some of which are involved in intracellular signaling pathways and may produce changes in neuronal function.
Keywords: Adolescent binge drinking; Alcohol Drinking; Alcohol-preferring rat; Amygdala; Animals; Central nucleus of the amygdala; Ethanol; Gene Expression; Gene Expression Regulation; Male; Nucleus accumbens-shell; Rats

Changes in gene expression within the extended amygdala following binge-like alcohol drinking by adolescent alcohol-preferring (P) rats - McBride, William J.; Kimpel, Mark W.; McClintick, Jeanette N.; Ding, Zheng-Ming; Edenberg, Howard J.; Liang, Tiebing; Rodd, Zachary A.; Bell, Richard L. (Pharmacology, Biochemistry, and Behavior, 2014)
The objective of this study was to determine changes in gene expression within the extended amygdala following binge-like alcohol drinking by male adolescent alcohol-preferring (P) rats. Starting at 28 days of age, P rats were given concurrent access to 15 and 30% ethanol for 3 one-h sessions/day for 5 consecutive days/week for 3 weeks. Rats were killed by decapitation 3 h after the first ethanol access session on the 15th day of drinking. RNA was prepared from micropunch samples of the nucleus accumbens shell (Acb-sh) and central nucleus of the amygdala (CeA). Ethanol intakes were 2.5-3.0 g/kg/session. There were 154 and 182 unique named genes that significantly differed (FDR=0.2) between the water and ethanol group in the Acb-sh and CeA, respectively. Gene Ontology (GO) analyses indicated that adolescent binge drinking produced changes in biological processes involved with cell proliferation and regulation of cellular structure in the Acb-sh, and in neuron projection and positive regulation of cellular organization in the CeA. Ingenuity Pathway Analysis indicated that, in the Acb-sh, there were several major intracellular signaling pathways (e.g., cAMP-mediated and protein kinase A signaling pathways) altered by adolescent drinking, with 3-fold more genes up-regulated than down-regulated in the alcohol group. The cAMP-mediated signaling system was also up-regulated in the CeA of the alcohol group. Weighted gene co-expression network analysis indicated significant G-protein coupled receptor signaling and transmembrane receptor protein kinase signaling categories in the Acb-sh and CeA, respectively. Overall, the results of this study indicated that binge-like alcohol drinking by adolescent P rats is differentially altering the expression of genes in the Acb-sh and CeA, some of which are involved in intracellular signaling pathways and may produce changes in neuronal function.
Keywords: Adolescent binge drinking; Alcohol Drinking; Alcohol-preferring rat; Amygdala; Animals; Central nucleus of the amygdala; Ethanol; Gene Expression; Gene Expression Regulation; Male; Nucleus accumbens-shell; Rats

Drinking alcohol has sex-dependent effects on pair bond formation in prairie voles - Anacker, Allison M.J.; Ahern, Todd H.; Hostetler, Caroline M.; Dufour, Brett D.; Smith, Monique L.; Cocking, Davelle L.; Li, Ju; Young, Larry J.; Loftis, Jennifer M.; Ryabinin, Andrey E. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Alcohol use and abuse profoundly influences a variety of behaviors, including social interactions. In some cases, it erodes social relationships; in others, it facilitates sociality. Here, we show that voluntary alcohol consumption can inhibit male partner preference (PP) formation (a laboratory proxy for pair bonding) in socially monogamous prairie voles (Microtus ochrogaster). Conversely, female PP is not inhibited, and may be facilitated by alcohol. Behavior and neurochemical analysis suggests that the effects of alcohol on social bonding are mediated by neural mechanisms regulating pair bond formation and not alcohol's effects on mating, locomotor, or aggressive behaviors. Several neuropeptide systems involved in the regulation of social behavior (especially neuropeptide Y and corticotropin-releasing factor) are modulated by alcohol drinking during cohabitation. These findings provide the first evidence to our knowledge that alcohol has a direct impact on the neural systems involved in social bonding in a sex-specific manner, providing an opportunity to explore the mechanisms by which alcohol affects social relationships.
Keywords: Aggression; Alcohol Drinking; Animal; Animals; Anxiety; Arvicolinae; Ethanol; Female; Male; Mating Preference; Neuropeptides; Oxytocin; Pair Bond; Proto-Oncogene Proteins c-fos; Sex Characteristics; substance use; vasopressin

"Drinking in the Dark" (DID): a simple mouse model of binge-like alcohol intake - Thiele, Todd E.; Crabbe, John C.; Boehm, Stephen L. (Current Protocols in Neuroscience, 2014)
One of the greatest challenges that scientists face when studying the neurobiology and/or genetics of alcohol (ethanol) consumption is that most preclinical animal models do not voluntarily consume enough ethanol to achieve pharmacologically meaningful blood ethanol concentrations (BECs). Recent rodent models have been developed that promote binge-like levels of ethanol consumption associated with high BECs (i.e., ≥100 mg/dl). This unit describes procedures for an animal model of binge-like ethanol drinking which has come to be called "drinking in the dark" (DID). The "basic" variation of DID involves replacing the water bottle with a bottle containing 20% ethanol for 2 to 4 hr, beginning 3 hr into the dark cycle, on cages of singly-housed C57BL/6J mice. Using this procedure, mice typically consume enough ethanol to achieve BECs >100 mg/dl and to exhibit behavioral evidence of intoxication. An alternative two-bottle (ethanol and water) procedure is also described.
Keywords: Animal; Animals; Binge Drinking; binge-like; Consumption; Darkness; Disease Models; Drinking-in-the-dark; Ethanol; Female; Inbred C57BL; limited-access; Male; Mice

Drinking songs: alcohol effects on learned song of zebra finches - Olson, Christopher R.; Owen, Devin C.; Ryabinin, Andrey E.; Mello, Claudio V. (PloS One, 2014)
Speech impairment is one of the most intriguing and least understood effects of alcohol on cognitive function, largely due to the lack of data on alcohol effects on vocalizations in the context of an appropriate experimental model organism. Zebra finches, a representative songbird and a premier model for understanding the neurobiology of vocal production and learning, learn song in a manner analogous to how humans learn speech. Here we show that when allowed access, finches readily drink alcohol, increase their blood ethanol concentrations (BEC) significantly, and sing a song with altered acoustic structure. The most pronounced effects were decreased amplitude and increased entropy, the latter likely reflecting a disruption in the birds' ability to maintain the spectral structure of song under alcohol. Furthermore, specific syllables, which have distinct acoustic structures, were differentially influenced by alcohol, likely reflecting a diversity in the neural mechanisms required for their production. Remarkably, these effects on vocalizations occurred without overt effects on general behavioral measures, and importantly, they occurred within a range of BEC that can be considered risky for humans. Our results suggest that the variable effects of alcohol on finch song reflect differential alcohol sensitivity of the brain circuitry elements that control different aspects of song production. They also point to finches as an informative model for understanding how alcohol affects the neuronal circuits that control the production of learned motor behaviors.
Keywords: Acoustics; Alcohol Drinking; Analysis of Variance; Animal; Animals; Ethanol; Finches; Learning; Male; Principal Component Analysis; Stereotyped Behavior; Vocalization

Dual-trait selection for ethanol consumption and withdrawal: genetic and transcriptional network effects - Metten, Pamela; Iancu, Ovidiu D.; Spence, Stephanie E.; Walter, Nicole A. R.; Oberbeck, Denesa; Harrington, Christina A.; Colville, Alexandre; McWeeney, Shannon; Phillips, Tamara J.; Buck, Kari J.; Crabbe, John C.; Belknap, John K.; et al. (Alcoholism, Clinical and Experimental Research, 2014)
BACKGROUND: Data from C57BL/6J (B6) × DBA/2J (D2) F2 intercrosses (B6xD2 F2 ), standard and recombinant inbred strains, and heterogeneous stock mice indicate that a reciprocal (or inverse) genetic relationship exists between alcohol consumption and withdrawal severity. Furthermore, some genetic studies have detected reciprocal quantitative trait loci (QTLs) for these traits. We used a novel mouse model developed by simultaneous selection for both high alcohol consumption/low withdrawal and low alcohol consumption/high withdrawal and analyzed the gene expression and genome-wide genotypic differences. METHODS: Randomly chosen third selected generation (S3 ) mice (N = 24/sex/line), bred from a B6xD2 F2 , were genotyped using the Mouse Universal Genotyping Array, which provided 2,760 informative markers. QTL analysis used a marker-by-marker strategy with the threshold for a significant log of the odds (LOD) set at 10. Gene expression in the ventral striatum was measured using the Illumina Mouse 8.2 array. Differential gene expression and the weighted gene co-expression network analysis (WGCNA) were implemented. RESULTS: Significant QTLs for consumption/withdrawal were detected on chromosomes (Chr) 2, 4, 9, and 12. A suggestive QTL mapped to Chr 6. Some of the QTLs overlapped with known QTLs mapped for 1 of the traits individually. One thousand seven hundred and forty-five transcripts were detected as being differentially expressed between the lines; there was some overlap with known withdrawal genes (e.g., Mpdz) located within QTL regions. WGCNA revealed several modules of co-expressed genes showing significant effects in both differential expression and intramodular connectivity; a module richly annotated with kinase-related annotations was most affected. CONCLUSIONS: Marked effects of selection on expression and network structure were detected. QTLs overlapping with differentially expressed genes on Chr 2 (distal) and 4 suggest that these are cis-eQTLs (Chr 2: Kif3b, Kcnq2; Chr 4: Mpdz, Snapc3). Other QTLs identified were on Chr 2 (proximal), 9, and 12. Network results point to involvement of kinase-related mechanisms and outline the need for further efforts such as interrogation of noncoding RNAs.
Keywords: Alcohol Consumption and Withdrawal; Alcohol Drinking; Animals; Breeding; Dual-Trait Selective Breeding; Female; Gene Regulatory Networks; Genetic; Inbred C57BL; Inbred DBA; Male; Mice; Microarray; Mouse; Quantitative Trait Loci; Species Specificity; Substance Withdrawal Syndrome; Transcription; Weighted Gene Co-Expression Network Analysis

The effects of ghrelin antagonists [D-Lys(3) ]-GHRP-6 or JMV2959 on ethanol, water, and food intake in C57BL/6J mice - Gomez, Juan L.; Ryabinin, Andrey E. (Alcoholism, Clinical and Experimental Research, 2014)
BACKGROUND: Alcohol use and abuse patterns have created a need for novel treatment models. Current research has turned its focus on reward pathways associated with intrinsic necessities, such as feeding. Theories suggest that drugs of abuse seize control of natural reward pathways and dysregulate normal function, leading to chronic addiction. One such pathway involving the hunger stimulating peptide, ghrelin, is the focus of our study. METHODS: Male C57BL/6J mice were randomly assigned to groups and treated with vehicle or a ghrelin antagonist, either [D-Lys(3) ]-GHRP-6 (DLys) or JMV2959. Three experiments tested ghrelin antagonism using different doses; experiment 1 tested 12 mg/kg JMV2959; experiment 2 tested 15 mg/kg DLys; experiment 3 tested 9 mg/kg JMV2959. Using a 2-bottle choice 24-hour access paradigm, data were collected for ethanol intake, preference, water intake, and food intake at 4 and 24 hours after injection. RESULTS: Experiment 1 showed that 12 mg/kg of JMV2959 decreased ethanol, water, and food intake, without affecting preference. Experiment 2 showed that 15 mg/kg of DLys decreased ethanol intake, preference, and water intake only on the first day of treatment. Experiment 3 showed that 9 mg/kg of JMV2959 decreased only ethanol and food intake. No change was seen during deprivation, and JMV2959 was still effective at reducing ethanol intake upon reintroduction. Despite the change in food intake, there were no differences in body weight throughout the experiments. It should be noted that the majority of significant effects were only found 4 hours postinjection. CONCLUSIONS: The results show that compounds that block ghrelin receptor activity are effective at decreasing ethanol intake. However, DLys was only effective at reducing intake and preference on the first day, suggesting a quick tolerance and selectivity for ethanol. JMV2959 consistently reduced ethanol intake, but at the higher dose also reduced all other consummatory behaviors. Thus, ghrelin antagonists provide a viable potential for treatment of alcohol abuse disorders, but further research is needed to determine an appropriate dose and administration paradigm.
Keywords: Alcohol Drinking; Animals; Drinking; Eating; Ethanol; Ghrelin; Ghrelin Antagonists; Glycine; Inbred C57BL; Male; Mice; Oligopeptides; Random Allocation; Receptors; self-administration; Treatment Outcome; Triazoles; Two-bottle choice

Establishment of stable dominance interactions in prairie vole peers: relationships with alcohol drinking and activation of the paraventricular nucleus of the hypothalamus - Anacker, Allison M.J.; Smith, Monique L.; Ryabinin, Andrey E. (Social Neuroscience, 2014)
Dominance hierarchies are an important aspect of group-living as they determine individual access to resources. The existence of dominance ranks in access to space has not been described in socially monogamous, communally nesting prairie voles (Microtus ochrogaster). Here, we tested whether dominance could be assessed using the tube test. We also tested whether dominance related to alcohol intake, similar to what has been demonstrated in nonmonogamous species. Same-sex pairs of unfamiliar peers were tested in a series of three trials of the tube test, then paired and allowed individual access to alcohol and water for 4 days, and then tested again in the tube test. For all pairs, the same subjects won the majority of trials before and after alcohol drinking. The number of wins negatively correlated with alcohol intake on the first day of drinking and positively correlated with levels of Fos in the paraventricular nucleus of the hypothalamus following the tube test in a separate group of voles. Dominance was not related to Fos levels in other brain regions examined. Together, these results indicate that prairie voles quickly establish stable dominance ranks through a process possibly involving the hypothalamus and suggest that dominance is linked to alcohol drinking.
Keywords: Aggression; Aging; Alcohol Drinking; Animals; Arvicolinae; Body Weight; Central Nervous System Depressants; CRF; Ethanol; Female; Immunohistochemistry; Male; Oxytocin; Paraventricular Hypothalamic Nucleus; Peer Group; Proto-Oncogene Proteins c-fos; Psychological Tests; Social dominance; Stress; vasopressin

Ethanol attenuation of long-term depression in the nucleus accumbens can be overcome by activation of TRPV1 receptors - Renteria, Rafael; Jeanes, Zachary M.; Morrisett, Richard A. (Alcoholism, Clinical and Experimental Research, 2014)
BACKGROUND: Altered expression of synaptic plasticity within the nucleus accumbens (NAc) constitutes a critical neuroadaptive response to ethanol (EtOH) and other drugs of abuse. We have previously reported that N-methyl-D-aspartate receptor (NMDAR)-dependent long-term depression (LTD) is markedly affected by chronic intermittent ethanol exposure in vivo; however, endocannabinoid (eCB)-dependent synaptic depression, despite being very well-documented in the dorsal striatum, is much less well understood in the NAc. METHODS: Whole cell patch clamp electrophysiology was used to investigate interactions between these different plasticity-induction systems. Excitatory postsynaptic currents (EPSCs) were measured in the NAc shell and NMDAR-LTD was induced by a pairing protocol (500 stimuli at 1 Hz stimulation [low-frequency stimulation (LFS)] paired with postsynaptic depolarization to -50 mV). AM251, a CB1 receptor antagonist, was used to determine whether this form of LTD is modulated by eCBs. To determine the effect of EtOH on a purely eCB-dependent response in the NAc, depolarization-induced suppression of excitation (DSE) was used in the presence of 40 mM EtOH. Finally, we determined whether the enhancement of eCB signaling with URB597, a fatty acid amide hydrolase inhibitor, and AM404, an anandamide re-uptake inhibitor would also modulate LFS LTD in the presence of NMDAR blockade or EtOH. RESULTS: In the presence of AM251, the LFS pairing protocol resulted in NMDAR-dependent long-term potentiation that was blocked with either EtOH or DL-APV. We also found that DSE in the NAc shell was blocked by AM251 and suppressed by EtOH. Enhanced eCB signaling rescued NAc-LTD expression in the presence of EtOH through a distinct mechanism requiring activation of TRPV1 receptors. CONCLUSIONS: EtOH modulation of synaptic plasticity in the NAc is dependent upon a complex interplay between NMDARs, eCBs, and TRPV1 receptors. These findings demonstrate a novel form of TRPV1-dependent LTD in the NAc shell that may be critical for EtOH dependence.
Keywords: Animals; Depolarization-Induced Suppression of Excitation; Electrophysiology; Endocannabinoid; Ethanol; Inbred C57BL; Long-Term Synaptic Depression; Male; Mice; Nucleus Accumbens; Organ Culture Techniques; Piperidines; Plasticity; Pyrazoles; TRPV Cation Channels; TRPV1

Experimenter effects on behavioral test scores of eight inbred mouse strains under the influence of ethanol - Bohlen, Martin; Hayes, Erika R.; Bohlen, Benjamin; Bailoo, Jeremy; Crabbe, John C.; Wahlsten, Douglas (Behavioural brain research, 2014)
Eight standard inbred mouse strains were evaluated for ethanol effects on a refined battery of behavioral tests in a study that was originally designed to assess the influence of rat odors in the colony on mouse behaviors. As part of the design of the study, two experimenters conducted the tests, and the study was carefully balanced so that equal numbers of mice in all groups and times of day were tested by each experimenter. A defect in airflow in the facility compromised the odor manipulation, and in fact the different odor exposure groups did not differ in their behaviors. The two experimenters, however, obtained markedly different results for three of the tests. Certain of the experimenter effects arose from the way they judged behaviors that were not automated and had to be rated by the experimenter, such as slips on the balance beam. Others were not evident prior to ethanol injection but had a major influence after the injection. For several measures, the experimenter effects were notably different for different inbred strains. Methods to evaluate and reduce the impact of experimenter effects in future research are discussed.

Expression of mu opioid receptor in dorsal diencephalic conduction system: new insights for the medial habenula - Gardon, O.; Faget, L.; Chu Sin Chung, P.; Matifas, A.; Massotte, D.; Kieffer, B. L. (Neuroscience, 2014)
The habenular complex, encompassing medial (MHb) and lateral (LHb) divisions, is a highly conserved epithalamic structure involved in the dorsal diencephalic conduction system (DDC). These brain nuclei regulate information flow between the limbic forebrain and the mid- and hindbrain, integrating cognitive with emotional and sensory processes. The MHb is also one of the strongest expression sites for mu opioid receptors (MORs), which mediate analgesic and rewarding properties of opiates. At present however, anatomical distribution and function of these receptors have been poorly studied in MHb pathways. Here we took advantage of a newly generated MOR-mcherry knock-in mouse line to characterize MOR expression sites in the DDC. MOR-mcherry fluorescent signal is weak in the LHb, but strong expression is visible in the MHb, fasciculus retroflexus (fr) and interpeduncular nucleus (IPN), indicating that MOR is mainly present in the MHb-IPN pathway. MOR-mcherry cell bodies are detected both in basolateral and apical parts of MHb, where the receptor co-localizes with cholinergic and substance P (SP) neurons, respectively, representing two main MHb neuronal populations. MOR-mcherry is expressed in most MHb-SP neurons, and is present in only a subpopulation of MHb-cholinergic neurons. Intense diffuse fluorescence detected in lateral and rostral parts of the IPN further suggests that MOR-mcherry is transported to terminals of these SP and cholinergic neurons. Finally, MOR-mcherry is present in septal regions projecting to the MHb, and in neurons of the central and intermediate IPN. Together, this study describes MOR expression in several compartments of the MHb-IPN circuitry. The remarkably high MOR density in the MHb-IPN pathway suggests that these receptors are in a unique position to mediate analgesic, autonomic and reward responses.
Keywords: 129 Strain; Acetylcholine; Animals; Enkephalins; Female; Gene Knock-In Techniques; Habenula; Immunohistochemistry; Inbred C57BL; Interpeduncular Nucleus; knock-in mice; Luminescent Proteins; Male; medial habenula; Mice; mu; mu opioid receptor; Neural Pathways; Neurons; Opioid; Protein Precursors; Receptors; Substance P; Transgenic

GABAA Receptors Containing ρ1 Subunits Contribute to In Vivo Effects of Ethanol in Mice - Blednov, Yuri A.; Benavidez, Jillian M.; Black, Mendy; Leiter, Courtney R.; Osterndorff-Kahanek, Elizabeth; Johnson, David; Borghese, Cecilia M.; Hanrahan, Jane R.; Johnston, Graham A. R.; Chebib, Mary; Harris, R. Adron (PLoS ONE, 2014)
GABAA receptors consisting of ρ1, ρ2, or ρ3 subunits in homo- or hetero-pentamers have been studied mainly in retina but are detected in many brain regions. Receptors formed from ρ1 are inhibited by low ethanol concentrations, and family-based association analyses have linked ρ subunit genes with alcohol dependence. We determined if genetic deletion of ρ1 in mice altered in vivo ethanol effects. Null mutant male mice showed reduced ethanol consumption and preference in a two-bottle choice test with no differences in preference for saccharin or quinine. Null mutant mice of both sexes demonstrated longer duration of ethanol-induced loss of righting reflex (LORR), and males were more sensitive to ethanol-induced motor sedation. In contrast, ρ1 null mice showed faster recovery from acute motor incoordination produced by ethanol. Null mutant females were less sensitive to ethanol-induced development of conditioned taste aversion. Measurement of mRNA levels in cerebellum showed that deletion of ρ1 did not change expression of ρ2, α2, or α6 GABAA receptor subunits. (S)-4-amino-cyclopent-1-enyl butylphosphinic acid (“ρ1” antagonist), when administered to wild type mice, mimicked the changes that ethanol induced in ρ1 null mice (LORR and rotarod tests), but the ρ1 antagonist did not produce these effects in ρ1 null mice. In contrast, (R)-4-amino-cyclopent-1-enyl butylphosphinic acid (“ρ2” antagonist) did not change ethanol actions in wild type but produced effects in mice lacking ρ1 that were opposite of the effects of deleting (or inhibiting) ρ1. These results suggest that ρ1 has a predominant role in two in vivo effects of ethanol, and a role for ρ2 may be revealed when ρ1 is deleted. We also found that ethanol produces similar inhibition of function of recombinant ρ1 and ρ2 receptors. These data indicate that ethanol action on GABAA receptors containing ρ1/ρ2 subunits may be important for specific effects of ethanol in vivo.

Genetic relationship between predisposition for binge alcohol consumption and blunted sensitivity to adverse effects of alcohol in mice - Fritz, Brandon M.; Cordero, Kristy A.; Barkley-Levenson, Amanda M.; Metten, Pamela; Crabbe, John C.; Boehm, Stephen L. (Alcoholism, Clinical and Experimental Research, 2014)
BACKGROUND: Initial sensitivity to ethanol (EtOH) and the capacity to develop acute functional tolerance (AFT) to its adverse effects may influence the amount of alcohol consumed and may also predict future alcohol use patterns. The current study assessed sensitivity and AFT to the ataxic and hypnotic effects of EtOH in the first replicate of mice (HDID-1) selectively bred for high blood EtOH concentrations (BECs) following limited access to EtOH in the Drinking in the Dark (DID) paradigm. METHODS: Naïve male and female HDID-1 and HS/Npt mice from the progenitor stock were evaluated in 3 separate experiments. In Experiments 1 and 2, EtOH-induced ataxia was assessed using the static dowel task. In Experiment 3, EtOH-induced hypnosis was assessed by using modified restraint tubes to measure the loss of righting reflex (LORR). RESULTS: HDID-1 mice exhibited reduced initial sensitivity to both EtOH-induced ataxia (p < 0.001) and hypnosis (p < 0.05) relative to HS/Npt mice. AFT was calculated by subtracting the BEC at loss of function from the BEC at recovery (Experiments 1 and 3) or by subtracting BEC at an initial recovery from the BEC at a second recovery following an additional alcohol dose (Experiment 2). The dowel test yielded no line differences in AFT, but HS/Npt mice developed slightly greater AFT to EtOH-induced LORR than HDID-1 (p < 0.05). CONCLUSIONS: These results suggest that HDID-1 mice exhibit aspects of blunted ataxic and hypnotic sensitivity to EtOH which may influence their high EtOH intake via DID, but do not display widely different development of AFT. These findings differ from previous findings with the high alcohol-preferring (HAP) selected mouse lines, suggesting that genetic predisposition for binge, versus other forms of excessive alcohol consumption, is associated with unique responses to EtOH-induced motor incoordination.
Keywords: Alcoholic Intoxication; Animals; Ataxia; Drug Tolerance; Ethanol; Female; Genetic Predisposition to Disease; High Drinking in the Dark Mice; Inbred Strains; Loss of Righting Reflex; Male; Mice; Reflex; Righting; Selected Mouse Lines

Genetics of gene expression characterizes response to selective breeding for alcohol preference - Hoffman, P. L.; Saba, L. M.; Flink, S.; Grahame, N. J.; Kechris, K.; Tabakoff, B. (Genes, Brain, and Behavior, 2014)
Numerous selective breeding experiments have been performed with rodents, in an attempt to understand the genetic basis for innate differences in preference for alcohol consumption. Quantitative trait locus (QTL) analysis has been used to determine regions of the genome that are associated with the behavioral difference in alcohol preference/consumption. Recent work suggests that differences in gene expression represent a major genetic basis for complex traits. Therefore, the QTLs are likely to harbor regulatory regions (eQTLs) for the differentially expressed genes that are associated with the trait. In this study, we examined brain gene expression differences over generations of selection of the third replicate lines of high and low alcohol-preferring (HAP3 and LAP3) mice, and determined regions of the genome that control the expression of these differentially expressed genes (de eQTLs). We also determined eQTL regions (rv eQTLs) for genes that showed a decrease in variance of expression levels over the course of selection. We postulated that de eQTLs that overlap with rv eQTLs, and also with phenotypic QTLs, represent genomic regions that are affected by the process of selection. These overlapping regions controlled the expression of candidate genes (that displayed differential expression and reduced variance of expression) for the predisposition to differences in alcohol consumption by the HAP3/LAP3 mice.
Keywords: Alcohol Drinking; Alcohol preference; Animals; Breeding; Choice Behavior; Gene Expression; Gene Expression Profiling; genetics of gene expression; Genotype; HAP and LAP mice; Mice; Phenotype; QTL analysis; Quantitative Trait Loci; Selective breeding

The genetics of gene expression in complex mouse crosses as a tool to study the molecular underpinnings of behavior traits - Hitzemann, Robert; Bottomly, Daniel; Iancu, Ovidiu; Buck, Kari; Wilmot, Beth; Mooney, Michael; Searles, Robert; Zheng, Christina; Belknap, John; Crabbe, John; McWeeney, Shannon (Mammalian Genome: Official Journal of the International Mammalian Genome Society, 2014)
Complex Mus musculus crosses provide increased resolution to examine the relationships between gene expression and behavior. While the advantages are clear, there are numerous analytical and technological concerns that arise from the increased genetic complexity that must be considered. Each of these issues is discussed, providing an initial framework for complex cross study design and planning.
Keywords: Animals; Behavioral; Crosses; Gene Expression; Genetic; Genetics; Genomics; Heritable; Mice; Phenotype; Population; Quantitative Trait; Quantitative Trait Loci

High drinking in the dark mice: a genetic model of drinking to intoxication - Barkley-Levenson, Amanda M.; Crabbe, John C. (Alcohol (Fayetteville, N.Y.), 2014)
Drinking to intoxication is a critical component of risky drinking behaviors in humans, such as binge drinking. Previous rodent models of alcohol consumption largely failed to demonstrate that animals were patterning drinking in such a way as to experience intoxication. Therefore, few rodent models of binge-like drinking and no specifically genetic models were available to study possible predisposing genes. The High Drinking in the Dark (HDID) selective breeding project was started to help fill this void, with HDID mice selected for reaching high blood alcohol levels in a limited access procedure. HDID mice now represent a genetic model of drinking to intoxication and can be used to help answer questions regarding predisposition toward this trait as well as potential correlated responses. They should also prove useful for the eventual development of better therapeutic strategies.
Keywords: Alcohol Drinking; Alcoholic Intoxication; Animal; Animals; Binge; Circadian Rhythm; Darkness; Disease Models; Drinking in the dark; Ethanol; Ethanol consumption; Genetics; Mice; Selective breeding

Identification of a QTL in Mus musculus for Alcohol Preference, Withdrawal, and Ap3m2 Expression Using Integrative Functional Genomics and Precision Genetics - Bubier, Jason A.; Jay, Jeremy J.; Baker, Christopher L.; Bergeson, Susan E.; Ohno, Hiroshi; Metten, Pamela; Crabbe, John C.; Chesler, Elissa J. (Genetics, 2014)
Extensive genetic and genomic studies of the relationship between alcohol drinking preference and withdrawal severity have been performed using animal models. Data from multiple such publications and public data resources have been incorporated in the GeneWeaver database with >60,000 gene sets including 285 alcohol withdrawal and preference-related gene sets. Among these are evidence for positional candidates regulating these behaviors in overlapping quantitative trait loci (QTL) mapped in distinct mouse populations. Combinatorial integration of functional genomics experimental results revealed a single QTL positional candidate gene in one of the loci common to both preference and withdrawal. Functional validation studies in Ap3m2 knockout mice confirmed these relationships. Genetic validation involves confirming the existence of segregating polymorphisms that could account for the phenotypic effect. By exploiting recent advances in mouse genotyping, sequence, epigenetics, and phylogeny resources, we confirmed that Ap3m2 resides in an appropriately segregating genomic region. We have demonstrated genetic and alcohol-induced regulation of Ap3m2 expression. Although sequence analysis revealed no polymorphisms in the Ap3m2-coding region that could account for all phenotypic differences, there are several upstream SNPs that could. We have identified one of these to be an H3K4me3 site that exhibits strain differences in methylation. Thus, by making cross-species functional genomics readily computable we identified a common QTL candidate for two related bio-behavioral processes via functional evidence and demonstrate sufficiency of the genetic locus as a source of variation underlying two traits.

Imaging neuroinflammation? A perspective from MR spectroscopy - Zahr, Natalie M.; Mayer, Dirk; Rohlfing, Torsten; Sullivan, Edith V.; Pfefferbaum, Adolf (Brain Pathology (Zurich, Switzerland), 2014)
Neuroinflammatory mechanisms contribute to the brain pathology resulting from human immunodeficiency virus (HIV) infection. Magnetic resonance spectroscopy (MRS) has been touted as a suitable method for discriminating in vivo markers of neuroinflammation. The present MRS study was conducted in four groups: alcohol dependent (A, n = 37), HIV-infected (H, n = 33), alcohol dependent + HIV infected (HA, n = 38) and healthy control (C, n = 62) individuals to determine whether metabolites would change in a pattern reflecting neuroinflammation. Significant four-group comparisons were evident only for striatal choline-containing compounds (Cho) and myo-inositol (mI), which follow-up analysis demonstrated were due to higher levels in HA compared with C individuals. To explore the potential relevance of elevated Cho and mI, correlations between blood markers, medication status and alcohol consumption were evaluated in H + HA subjects. Having an acquired immune deficiency syndrome (AIDS)-defining event or hepatitis C was associated with higher Cho; lower Cho levels, however, were associated with low thiamine levels and with highly active antiretroviral HIV treatment (HAART). Higher levels of mI were related to greater lifetime alcohol consumed, whereas HAART was associated with lower mI levels. The current results suggest that competing mechanisms can influence in vivo Cho and mI levels, and that elevations in these metabolites cannot necessarily be interpreted as reflecting a single underlying mechanism, including neuroinflammation.
Keywords: 80 and over; Acquired Immunodeficiency Syndrome; Adult; Aged; alcoholism; Antiretroviral Therapy; Brain; Choline; Female; Follow-Up Studies; Hepatitis C; Highly Active; HIV Infections; Humans; In vivo; Inositol; Magnetic Resonance Spectroscopy; Male; Middle Aged; myo-inositol; Neuroimmunomodulation; Thiamine; Young Adult

Increased behavioral responses to ethanol in Lmo3 knockout mice - Savarese, A.; Zou, M. E.; Kharazia, V.; Maiya, R.; Lasek, A. W. (Genes, Brain, and Behavior, 2014)
LIM-domain-only 3 (LMO3) is a transcriptional regulator involved in central nervous system development and neuroblastoma. Our previous studies implicated a potential role for LMO3 in regulating ethanol sensitivity and consumption. Here, we examined behavioral responses to ethanol in a line of Lmo3 null (Lmo3(Z) ) mice, utilizing the ethanol-induced loss-of-righting-reflex (LORR) test, two-bottle choice ethanol consumption and the drinking in the dark (DID) test, which models binge-like ethanol consumption. We found that Lmo3(Z) mice exhibited increased sedation time in response to ethanol in the LORR test and drank significantly more ethanol in the DID test compared with their wild-type counterparts, but showed no differences in two-bottle choice ethanol consumption. To explore where LMO3 may be acting in the brain to produce an ethanol phenotype, we also examined reporter gene (β-galactosidase) expression in heterozygous Lmo3(Z) mice and found strong expression in subcortical areas, particularly in those areas implicated in drug abuse, including the nucleus accumbens (Acb), cortex, hippocampus and amygdala. We also examined Lmo3 expression in the brains of wild-type mice who had undergone the DID test and found a negative correlation between Lmo3 expression in the Acb and the amount of ethanol consumed, consistent with the increased binge-like drinking observed in Lmo3(Z) mice. These results support a role for LMO3 in regulating behavioral responses to ethanol, potentially through its actions in the Acb.
Keywords: Adaptor Proteins; Alcohol Drinking; Animal; Animals; Behavior; Binge Drinking; Brain; Choice Behavior; Ethanol; Knockout; LIM Domain Proteins; LMO3; Mice; sedation; Signal Transducing

INFERRING TRANSCRIPTIONAL REGULATION THROUGH LOGICAL NETWORKS FROM TEMPORAL MOUSE BRAIN GENE EXPRESSION DATA - Song, Mingzhou (joe; Lewis, Chris K.; Lance, Eric R.; Chesler, Elissa J.; Kirova, Roumyana; Langston, Michael A.; Bergeson, Susan E. (2014)
Abstract: The problem of computing logical network models to account for temporal dependencies among interacting genes and environmental stimuli from high-throughput transcriptomic data is addressed. A logical network reconstruction algorithm was developed that uses the statistical significance as a criterion for network selection to avoid false interactions arising from pure chance. Using temporal gene expression data collected from the brains of alcohol-treated mice in an analysis of the molecular response to alcohol, this algorithm identified several genes from a major neuronal pathway as putative components of the alcohol response mechanism. Three of these genes have known specific associations with alcohol response as reported in the literature. Several other potentially relevant genes were also highlighted, in agreement with independent results from literature mining. These genes may play a role in the response to alcohol. Additional, previously-unknown interactions were discovered in the logical network that, subject to biological verification, may offer new clues in the search for the elusive molecular mechanisms of alcoholism.

Inhibition of phosphodiesterase 4 reduces ethanol intake and preference in C57BL/6J mice - Blednov, Yuri A.; Benavidez, Jillian M.; Black, Mendy; Harris, R. Adron (Frontiers in Neuroscience, 2014)
Some anti-inflammatory medications reduce alcohol consumption in rodent models. Inhibition of phosphodiesterases (PDE) increases cAMP and reduces inflammatory signaling. Rolipram, an inhibitor of PDE4, markedly reduced ethanol intake and preference in mice and reduced ethanol seeking and consumption in alcohol-preferring fawn-hooded rats (Hu et al., ; Wen et al., ). To determine if these effects were specific for PDE4, we compared nine PDE inhibitors with different subtype selectivity: propentofylline (nonspecific), vinpocetine (PDE1), olprinone, milrinone (PDE3), zaprinast (PDE5), rolipram, mesopram, piclamilast, and CDP840 (PDE4). Alcohol intake was measured in C57BL/6J male mice using 24-h two-bottle choice and two-bottle choice with limited (3-h) access to alcohol. Only the selective PDE4 inhibitors reduced ethanol intake and preference in the 24-h two-bottle choice test. For rolipram, piclamilast, and CDP840, this effect was observed after the first 6 h but not after the next 18 h. Mesopram, however, produced a long-lasting reduction of ethanol intake and preference. In the limited access test, rolipram, piclamilast, and mesopram reduced ethanol consumption and total fluid intake and did not change preference for ethanol, whereas CDP840 reduced both consumption and preference without altering total fluid intake. Our results provide novel evidence for a selective role of PDE4 in regulating ethanol drinking in mice. We suggest that inhibition of PDE4 may be an unexplored target for medication development to reduce excessive alcohol consumption.

Innate immune factors modulate ethanol interaction with GABAergic transmission in mouse central amygdala - Bajo, Michal; Madamba, Samuel G.; Roberto, Marisa; Blednov, Yuri A.; Sagi, Vasudeva N.; Roberts, Edward; Rice, Kenner C.; Harris, R. Adron; Siggins, George R. (Brain, Behavior, and Immunity, 2014)
Excessive ethanol drinking in rodent models may involve activation of the innate immune system, especially toll-like receptor 4 (TLR4) signaling pathways. We used intracellular recording of evoked GABAergic inhibitory postsynaptic potentials (eIPSPs) in central amygdala (CeA) neurons to examine the role of TLR4 activation by lipopolysaccharide (LPS) and deletion of its adapter protein CD14 in acute ethanol effects on the GABAergic system. Ethanol (44, 66 or 100mM) and LPS (25 and 50μg/ml) both augmented eIPSPs in CeA of wild type (WT) mice. Ethanol (44mM) decreased paired-pulse facilitation (PPF), suggesting a presynaptic mechanism of action. Acute LPS (25μg/ml) had no effect on PPF and significantly increased the mean miniature IPSC amplitude, indicating a postsynaptic mechanism of action. Acute LPS pre-treatment potentiated ethanol (44mM) effects on eIPSPs in WT mice and restored ethanol's augmenting effects on the eIPSP amplitude in CD14 knockout (CD14 KO) mice. Both the LPS and ethanol (44-66mM) augmentation of eIPSPs was diminished significantly in most CeA neurons of CD14 KO mice; however, ethanol at the highest concentration tested (100mM) still increased eIPSP amplitudes. By contrast, ethanol pre-treatment occluded LPS augmentation of eIPSPs in WT mice and had no significant effect in CD14 KO mice. Furthermore, (+)-naloxone, a TLR4-MD-2 complex inhibitor, blocked LPS effects on eIPSPs in WT mice and delayed the ethanol-induced potentiation of GABAergic transmission. In CeA neurons of CD14 KO mice, (+)-naloxone alone diminished eIPSPs, and subsequent co-application of 100mM ethanol restored the eIPSPs to baseline levels. In summary, our results indicate that TLR4 and CD14 signaling play an important role in the acute ethanol effects on GABAergic transmission in the CeA and support the idea that CD14 and TLR4 may be therapeutic targets for treatment of alcohol abuse.
Keywords: alcohol; Animals; Antigens; CD14; Central Amygdaloid Nucleus; drug abuse; Ethanol; Extended amygdala; GABA-A; Immunity; Immunologic Factors; Inbred C57BL; Inflammation; Inhibitory Postsynaptic Potentials; Innate; Knockout; Lipopolysaccharides; LPS; Male; Mice; Neuroimmune; Neurons; Receptors; Synaptic Transmission; Toll-like receptor; Toll-Like Receptor 4

Introduction to sequencing the brain transcriptome - Hitzemann, Robert; Darakjian, Priscila; Walter, Nikki; Iancu, Ovidiu Dan; Searles, Robert; McWeeney, Shannon (International Review of Neurobiology, 2014)
High-throughput next-generation sequencing is now entering its second decade. However, it was not until 2008 that the first report of sequencing the brain transcriptome appeared (Mortazavi, Williams, Mccue, Schaeffer, & Wold, 2008). These authors compared short-read RNA-Seq data for mouse whole brain with microarray results for the same sample and noted both the advantages and disadvantages of the RNA-Seq approach. While RNA-Seq provided exon level resolution, the majority of the reads were provided by a small proportion of highly expressed genes and the data analysis was exceedingly complex. Over the past 6 years, there have been substantial improvements in both RNA-Seq technology and data analysis. This volume contains 11 chapters that detail various aspects of sequencing the brain transcriptome. Some of the chapters are very methods driven, while others focus on the use of RNA-Seq to study such diverse areas as development, schizophrenia, and drug abuse. This chapter briefly reviews the transition from microarrays to RNA-Seq as the preferred method for analyzing the brain transcriptome. Compared with microarrays, RNA-Seq has a greater dynamic range, detects both coding and noncoding RNAs, is superior for gene network construction, detects alternative spliced transcripts, and can be used to extract genotype information, e.g., nonsynonymous coding single nucleotide polymorphisms. RNA-Seq embraces the complexity of the brain transcriptome and provides a mechanism to understand the underlying regulatory code; the potential to inform the brain-behavior-disease relationships is substantial.
Keywords: Animals; Behavior; Brain; Gene Expression Profiling; Gene Regulatory Networks; High-Throughput Nucleotide Sequencing; Humans; Next-generation sequencing; Oligonucleotide Array Sequence Analysis; RNA; RNA-seq; Transcriptome

MeCP2 regulates ethanol sensitivity and intake - Repunte-Canonigo, Vez; Chen, Jihuan; Lefebvre, Celine; Kawamura, Tomoya; Kreifeldt, Max; Basson, Oan; Roberts, Amanda J.; Sanna, Pietro Paolo (Addiction Biology, 2014)
We have investigated the expression of chromatin-regulating genes in the prefrontal cortex and in the shell subdivision of the nucleus accumbens during protracted withdrawal in mice with increased ethanol drinking after chronic intermittent ethanol (CIE) vapor exposure and in mice with a history of non-dependent drinking. We observed that the methyl-CpG binding protein 2 (MeCP2) was one of the few chromatin-regulating genes to be differentially regulated by a history of dependence. As MeCP2 has the potential of acting as a broad gene regulator, we investigated sensitivity to ethanol and ethanol drinking in MeCP2(308/) (Y) mice, which harbor a truncated MeCP2 allele but have a milder phenotype than MeCP2 null mice. We observed that MeCP2(308/) (Y) mice were more sensitive to ethanol's stimulatory and sedative effects than wild-type (WT) mice, drank less ethanol in a limited access 2 bottle choice paradigm and did not show increased drinking after induction of dependence with exposure to CIE vapors. Alcohol metabolism did not differ in MeCP2(308/) (Y) and WT mice. Additionally, MeCP2(308/) (Y) mice did not differ from WT mice in ethanol preference in a 24-hour paradigm nor in their intake of graded solutions of saccharin or quinine, suggesting that the MeCP2(308/) (Y) mutation did not alter taste function. Lastly, using the Gene Set Enrichment Analysis algorithm, we found a significant overlap in the genes regulated by alcohol and by MeCP2. Together, these results suggest that MeCP2 contributes to the regulation of ethanol sensitivity and drinking.
Keywords: Alcohol dependence; Alcohol Drinking; alcoholism; Animals; Central Nervous System Depressants; Chromatin; Dose-Response Relationship; Drug; epigenetic; Ethanol; Gene Expression; gene regulation; Hemizygote; Inbred C57BL; Male; Methyl-CpG-Binding Protein 2; Mice; Nucleus Accumbens; Prefrontal Cortex; Substance Withdrawal Syndrome; Taste

Molecular basis of alcoholism - Most, Dana; Ferguson, Laura; Harris, R. Adron (Handbook of Clinical Neurology, 2014)
Acute alcohol intoxication causes cellular changes in the brain that last for hours, while chronic alcohol use induces widespread neuroadaptations in the nervous system that can last a lifetime. Chronic alcohol use and the progression into dependence involve the remodeling of synapses caused by changes in gene expression produced by alcohol. The progression of alcohol use, abuse, and dependence can be divided into stages, which include intoxication, withdrawal, and craving. Each stage is associated with specific changes in gene expression, cellular function, brain circuits, and ultimately behavior. What are the molecular mechanisms underlying the transition from recreational use (acute) to dependence (chronic)? What cellular adaptations result in drug memory retention, leading to the persistence of addictive behaviors, even after prolonged drug abstinence? Research into the neurobiology of alcoholism aims to answer these questions. This chapter will describe the molecular adaptations caused by alcohol use and dependence, and will outline key neurochemical participants in alcoholism at the molecular level, which are also potential targets for therapy.
Keywords: alcoholism; Animals; Brain; dependence; dopamine; GABA; glutamate; Humans; microRNA; MicroRNAs; mRNA; neuroadaptations; Neuroimmune; Neurotransmitter; Receptors; Signal Transduction

Monkeys that voluntarily and chronically drink alcohol damage their brains: a longitudinal MRI study - Kroenke, Christopher D.; Rohlfing, Torsten; Park, Byung; Sullivan, Edith V.; Pfefferbaum, Adolf; Grant, Kathleen A. (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2014)
Neuroimaging has consistently documented reductions in the brain tissue of alcoholics. Inability to control comorbidity, environmental insult, and nutritional deficiency, however, confound the ability to assess whether ethanol itself is neurotoxic. Here we report monkey oral ethanol self-administration combined with MR imaging to characterize brain changes over 15 months in 18 well-nourished rhesus macaques. Significant brain volume shrinkage occurred in the cerebral cortices of monkeys drinking ≥ 3 g/kg ethanol/day (12 alcoholic drinks) at 6 months, and this persisted throughout the period of continuous access to ethanol. Correlation analyses revealed a cerebral cortical volumetric loss of ~0.11% of the intracranial vault for each daily drink (0.25 g/kg), and selective vulnerability of cortical and non-cortical brain regions. These results demonstrate for the first time a direct relation between oral ethanol intake and measures of decreased brain gray matter volume in vivo in primates. Notably, greater volume shrinkage occurred in monkeys with younger drinking onset that ultimately became heavier drinkers than monkeys with older drinking onset. The pattern of volumetric changes observed in nonhuman primates following 15 months of drinking suggests that cerebral cortical gray matter changes are the first macroscopic manifestation of chronic ethanol exposure in the brain.
Keywords: Administration; Analysis of Variance; Animals; Brain Damage; Brain Mapping; Central Nervous System Depressants; Chronic; Computer-Assisted; Ethanol; Image Processing; Longitudinal Studies; Macaca mulatta; Magnetic Resonance Imaging; Male; Oral; Self Administration; Statistics as Topic; Time Factors

Mu Opioid Receptors Mediate the Effects of Chronic Ethanol Binge Drinking on the Hippocampal Neurogenic Niche - Contet, Candice; Kim, Airee; Le, David; Iyengar, Siddharth; Kotzebue, Roxanne W.; Yuan, Clara J.; Kieffer, Brigitte L.; Mandyam, Chitra D. (Addiction biology, 2014)
Ethanol exposure and withdrawal alter the generation of new neurons in the adult hippocampus. The endogenous opioid system, in particular the μ opioid receptor (MOR), can modulate neural progenitors and also plays a critical role in ethanol drinking and dependence. In the present study, we sought to determine whether MOR contributes to the effects of ethanol on the dentate gyrus (DG) neurogenic niche. MOR wild-type (WT), heterozygous (Het) and knockout (KO) littermates were subjected to voluntary ethanol drinking in repeated limited-access two-bottle choice (2BC) sessions. MOR deficiency did not alter progenitor proliferation, neuronal differentiation and maturation, apoptosis or microglia in ethanol-naïve mice. When exposed to five consecutive weeks of 2BC, MOR mutant mice exhibited a gene-dosage dependent reduction of ethanol consumption compared to WT mice. Introducing a week of ethanol deprivation between each week of 2BC increased ethanol consumption in all genotypes and produced equivalent intakes in WT, Het and KO mice. Under the latter paradigm, ethanol drinking decreased progenitor proliferation and neuronal differentiation in the DG of WT mice. Interestingly, WT mice exhibited a strong negative correlation between ethanol intake and proliferation, which was disrupted in Het and KO mice. Moreover, MOR deficiency blocked the effect of ethanol on neuronal differentiation. MOR deficiency also protected against the neuroimmune response to ethanol drinking. Finally, chronic binge drinking induced a paradoxical decrease in apoptosis, which was independent of MOR. Altogether our data suggest that MOR is implicated in some of the neuroplastic changes produced by chronic ethanol exposure in the DG.

Neuroimmune mechanisms of alcohol and drug addiction - Cui, Changhai; Shurtleff, David; Harris, R. Adron (International Review of Neurobiology, 2014)
Alcohol and other drugs of abuse have significant impacts on the neuroimmune system. Studies have demonstrated that drugs of abuse interact with the neuroimmune system and alter neuroimmune gene expression and signaling, which in turn contribute to various aspects of addiction. As the key component of the CNS immune system, neuroimmune factors mediate neuroinflammation and modulate a wide range of brain function including neuronal activity, endocrine function, and CNS development. These neuromodulatory properties of immune factors, together with their essential role in neuroinflammation, provide a new framework to understand neuroimmune mechanisms mediating brain functional and behavioral changes contributing to addiction. This chapter highlights recent advances in understanding neuroimmune changes associated with exposure to alcohol and other drugs of abuse, including opiates, marijuana, methamphetamine, and cocaine. It provides a brief overview on what we know about neuroimmune signaling and its role in drug action and addiction.
Keywords: addiction; alcohol; Alcohols; Animals; Central Nervous System; Chemokine; Cytokine; Drugs of abuse; Gene Expression Regulation; Humans; Microglia; Neuroimmune; Neuroimmunomodulation; Neuroinflammation; Signal Transduction; Street Drugs

Neuroimmune pathways in alcohol consumption: evidence from behavioral and genetic studies in rodents and humans - Robinson, Gizelle; Most, Dana; Ferguson, Laura B.; Mayfield, Jody; Harris, R. Adron; Blednov, Yuri A. (International Review of Neurobiology, 2014)
Immune or brain proinflammatory signaling has been linked to some of the behavioral effects of alcohol. Immune signaling appears to regulate voluntary ethanol intake in rodent models, and ethanol intake activates the immune system in multiple models. This bidirectional link raises the possibility that consumption increases immune signaling, which in turn further increases consumption in a feed-forward cycle. Data from animal and human studies provide overlapping support for the involvement of immune-related genes and proteins in alcohol action, and combining animal and human data is a promising approach to systematically evaluate and nominate relevant pathways. Based on rodent models, neuroimmune pathways may represent unexplored, nontraditional targets for medication development to reduce alcohol consumption and prevent relapse. Peroxisome proliferator-activated receptor agonists are one class of anti-inflammatory medications that demonstrate antiaddictive properties for alcohol and other drugs of abuse. Expression of immune-related genes is altered in animals and humans following chronic alcohol exposure, and the regulatory influences of specific mRNAs, microRNAs, and activated cell types are areas of intense study. Ultimately, the use of multiple datasets combined with behavioral validation will be needed to link specific neuroimmune pathways to addiction vulnerability.
Keywords: Addictive; Alcohol Drinking; Animals; Behavior; Biological; dependence; Encephalitis; Ethanol; Gene Expression; Gene Expression Regulation; Human alcoholics; Humans; Knock-out mice; LPS; microRNA; Models; mRNA; Neuroimmunomodulation; PPAR; Preference; Rodentia; Signal Transduction; TLR4; Two-bottle choice

Operant alcohol self-administration in dependent rats: focus on the vapor model - Vendruscolo, Leandro F.; Roberts, Amanda J. (Alcohol (Fayetteville, N.Y.), 2014)
Alcoholism (alcohol dependence) is characterized by a compulsion to seek and ingest alcohol (ethanol), loss of control over intake, and the emergence of a negative emotional state during withdrawal. Animal models are critical in promoting our knowledge of the neurobiological mechanisms underlying alcohol dependence. Here, we review the studies involving operant alcohol self-administration in rat models of alcohol dependence and withdrawal with the focus on the alcohol vapor model. In 1996, the first articles were published reporting that rats made dependent on alcohol by exposure to alcohol vapors displayed increased operant alcohol self-administration during acute withdrawal compared with nondependent rats (i.e., not exposed to alcohol vapors). Since then, it has been repeatedly demonstrated that this model reliably produces physical and motivational symptoms of alcohol dependence. The functional roles of various systems implicated in stress and reward, including opioids, dopamine, corticotropin-releasing factor (CRF), glucocorticoids, neuropeptide Y (NPY), γ-aminobutyric acid (GABA), norepinephrine, and cannabinoids, have been investigated in the context of alcohol dependence. The combination of models of alcohol withdrawal and dependence with operant self-administration constitutes an excellent tool to investigate the neurobiology of alcoholism. In fact, this work has helped lay the groundwork for several ongoing clinical trials for alcohol dependence. Advantages and limitations of this model are discussed, with an emphasis on what future directions of great importance could be.
Keywords: addiction; Alcohol (ethanol) vapor; Alcohol dependence; Alcohol Drinking; alcoholism; Animal; Animals; Compulsive behavior; Conditioning; Disease Models; Ethanol; Operant; Operant self-administration; rat; Rats; Review; Self Administration

P2X4 receptors (P2X4Rs) represent a novel target for the development of drugs to prevent and/or treat alcohol use disorders - Franklin, Kelle M.; Asatryan, Liana; Jakowec, Michael W.; Trudell, James R.; Bell, Richard L.; Davies, Daryl L. (Frontiers in Neuroscience, 2014)
Alcohol use disorders (AUDs) have a staggering socioeconomic impact. Few therapeutic options are available, and they are largely inadequate. These shortcomings highlight the urgent need to develop effective medications to prevent and/or treat AUDs. A critical barrier is the lack of information regarding the molecular target(s) by which ethanol (EtOH) exerts its pharmacological activity. This review highlights findings implicating P2X4 receptors (P2X4Rs) as a target for the development of therapeutics to treat AUDs and discusses the use of ivermectin (IVM) as a potential clinical tool for treatment of AUDs. P2XRs are a family of ligand-gated ion channels (LGICs) activated by extracellular ATP. Of the P2XR subtypes, P2X4Rs are expressed the most abundantly in the CNS. Converging evidence suggests that P2X4Rs are involved in the development and progression of AUDs. First, in vitro studies report that pharmacologically relevant EtOH concentrations can negatively modulate ATP-activated currents. Second, P2X4Rs in the mesocorticolimbic dopamine system are thought to play a role in synaptic plasticity and are located ideally to modulate brain reward systems. Third, alcohol-preferring (P) rats have lower functional expression of the p2rx4 gene than alcohol-non-preferring (NP) rats suggesting an inverse relationship between alcohol intake and P2X4R expression. Similarly, whole brain p2rx4 expression has been shown to relate inversely to innate 24 h alcohol preference across 28 strains of rats. Fourth, mice lacking the p2rx4 gene drink more EtOH than wildtype controls. Fifth, IVM, a positive modulator of P2X4Rs, antagonizes EtOH-mediated inhibition of P2X4Rs in vitro and reduces EtOH intake and preference in vivo. These findings suggest that P2X4Rs contribute to EtOH intake. The present review summarizes recent findings focusing on the P2X4R as a molecular target of EtOH action, its role in EtOH drinking behavior and modulation of its activity by IVM as a potential therapy for AUDs.
Keywords: Alcohol-preferring; alcoholism; Ivermectin; p2rx4; P2X; P2X4 receptor; purinergic

PPAR agonists regulate brain gene expression: relationship to their effects on ethanol consumption - Ferguson, Laura B.; Most, Dana; Blednov, Yuri A.; Harris, R. Adron (Neuropharmacology, 2014)
Peroxisome proliferator-activated receptors (PPARs) are nuclear hormone receptors that act as ligand-activated transcription factors. Although prescribed for dyslipidemia and type-II diabetes, PPAR agonists also possess anti-addictive characteristics. PPAR agonists decrease ethanol consumption and reduce withdrawal severity and susceptibility to stress-induced relapse in rodents. However, the cellular and molecular mechanisms facilitating these properties have yet to be investigated. We tested three PPAR agonists in a continuous access two-bottle choice (2BC) drinking paradigm and found that tesaglitazar (PPARα/γ; 1.5 mg/kg) and fenofibrate (PPARα; 150 mg/kg) decreased ethanol consumption in male C57BL/6J mice while bezafibrate (PPARα/γ/β; 75 mg/kg) did not. We hypothesized that changes in brain gene expression following fenofibrate and tesaglitazar treatment lead to reduced ethanol drinking. We studied unbiased genomic profiles in areas of the brain known to be important for ethanol dependence, the prefrontal cortex (PFC) and amygdala, and also profiled gene expression in liver. Genomic profiles from the non-effective bezafibrate treatment were used to filter out genes not associated with ethanol consumption. Because PPAR agonists are anti-inflammatory, they would be expected to target microglia and astrocytes. Surprisingly, PPAR agonists produced a strong neuronal signature in mouse brain, and fenofibrate and tesaglitazar (but not bezafibrate) targeted a subset of GABAergic interneurons in the amygdala. Weighted gene co-expression network analysis (WGCNA) revealed co-expression of treatment-significant genes. Functional annotation of these gene networks suggested that PPAR agonists might act via neuropeptide and dopaminergic signaling pathways in the amygdala. Our results reveal gene targets through which PPAR agonists can affect alcohol consumption behavior.
Keywords: alcohol; Alcohol Drinking; Alkanesulfonates; Amygdala; Animals; Bezafibrate; Central Nervous System Agents; Central Nervous System Depressants; Drinking; Drinking Water; Ethanol; Fenofibrate; Gene Expression; Inbred C57BL; Liver; Male; Mice; Microarray; Peroxisome Proliferator-Activated Receptors; Phenylpropionates; PPAR; Prefrontal Cortex; Taste Perception

Presynaptic BK channels modulate ethanol-induced enhancement of GABAergic transmission in the rat central amygdala nucleus - Li, Qiang; Madison, Roger; Moore, Scott D. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2014)
Large-conductance calcium-activated potassium BK channels are widely expressed in the brain and are involved in the regulation of neuronal functions such as neurotransmitter release. However, their possible role in mediating ethanol-induced GABA release is still unknown. We assessed the role of BK channels in modulating the action of ethanol on inhibitory synaptic transmission mediated via GABAA receptors in the rat central nucleus of the amygdala (CeA). Evoked IPSCs (eIPSCs) mediated by GABAA receptors were isolated from CeA neurons under whole-cell voltage clamp, and their response to selective BK channel antagonists, channel activators, or ethanol was analyzed. Blocking BK channels with the specific BK channel antagonist paxilline significantly increased the mean amplitude of eIPSCs, whereas the activation of BK channels with the channel opener NS1619 reversibly attenuated the mean amplitude of eIPSCs. Ethanol (50 mM) alone enhanced the amplitude of eIPSCs but failed to further enhance eIPSCs in the slices pretreated with paxilline. Bath application of either BK channel blockers significantly increased the frequency of miniature IPSCs (mIPSCs). Similarly, 50 mM ethanol alone also enhanced mIPSC frequency. Increases in mIPSC frequency by either selective BK channel antagonists or ethanol were not accompanied with changes in the amplitude of mIPSCs. Furthermore, following bath application of BK channel blockers for 10 min, ethanol failed to further increase mIPSC frequency. Together, these results suggest that blocking BK channels mimics the effects of ethanol on GABA release and that presynaptic BK channels could serve as a target for ethanol effects in CeA.
Keywords: Amygdala; Animals; anxiolytic; Calcium Channels; Central Nervous System Depressants; Ethanol; Excitatory Postsynaptic Potentials; GABA; gamma-Aminobutyric Acid; In Vitro Techniques; inhibition; Large-Conductance Calcium-Activated Potassium Channels; Male; Potassium; Potassium Channel Blockers; presynaptic; Presynaptic Terminals; Rats; Sprague-Dawley; Synaptic Transmission

Progress in a replicated selection for elevated blood ethanol concentrations in HDID mice - Crabbe, J. C.; Metten, P.; Belknap, J. K.; Spence, S. E.; Cameron, A. J.; Schlumbohm, J. P.; Huang, L. C.; Barkley-Levenson, A. M.; Ford, M. M.; Phillips, T. J. (Genes, Brain, and Behavior, 2014)
Drinking in the dark (DID) is a limited access ethanol-drinking phenotype in mice. High Drinking in the Dark (HDID-1) mice have been bred for 27 selected generations (S27) for elevated blood ethanol concentrations (BECs) after a 4-h period of access to 20% ethanol. A second replicate line (HDID-2) was started later from the same founder population and is currently in S20. An initial report of response to selection in HDID-1 was published after S11. This article reports genetic and behavioral characteristics of both lines in comparison with the HS controls. Heritability is low in both replicates (h(2)  = 0.09) but the lines have shown 4-5 fold increases in BEC since S0; 80% of HDID-1 and 60% of HDID-2 mice reach BECs greater than 1.0 mg/ml. Several hours after a DID test, HDID mice show mild signs of withdrawal. Although not considered during selection, intake of ethanol (g/kg) during the DID test increased by approximately 80% in HDID-1 and 60% in HDID-2. Common genetic influences were more important than environmental influences in determining the similarity between BEC and intake for HDID mice. Analysis of the partitioning of intake showed that 60% of intake is concentrated in the last 2 h of the 4 h session. However, this has not changed during selection. Hourly BECs during the DID test reach peak levels after 3 or 4 h of drinking. HDID mice do not differ from HS mice in their rate of elimination of an acute dose of alcohol.
Keywords: Animals; Binge; Binge Drinking; Ethanol; Ethanol consumption; Ethanol withdrawal; Female; Genetic; Genetics; Inbreeding; Male; Mice; Selection; Selective breeding

Proteomic approaches and identification of novel therapeutic targets for alcoholism - Gorini, Giorgio; Harris, R. Adron; Mayfield, R. Dayne (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2014)
Recent studies have shown that gene regulation is far more complex than previously believed and does not completely explain changes at the protein level. Therefore, the direct study of the proteome, considerably different in both complexity and dynamicity to the genome/transcriptome, has provided unique insights to an increasing number of researchers. During the past decade, extraordinary advances in proteomic techniques have changed the way we can analyze the composition, regulation, and function of protein complexes and pathways underlying altered neurobiological conditions. When combined with complementary approaches, these advances provide the contextual information for decoding large data sets into meaningful biologically adaptive processes. Neuroproteomics offers potential breakthroughs in the field of alcohol research by leading to a deeper understanding of how alcohol globally affects protein structure, function, interactions, and networks. The wealth of information gained from these advances can help pinpoint relevant biomarkers for early diagnosis and improved prognosis of alcoholism and identify future pharmacological targets for the treatment of this addiction.
Keywords: alcoholism; Animals; Biomarkers; Brain; Drug Discovery; Gene Expression Regulation; Humans; Ion Channels; Molecular Targeted Therapy; Proteomics; Systems Biology

Rat strain differences in brain structure and neurochemistry in response to binge alcohol - Zahr, Natalie M.; Mayer, Dirk; Rohlfing, Torsten; Hsu, Oliver; Vinco, Shara; Orduna, Juan; Luong, Richard; Bell, Richard L.; Sullivan, Edith V.; Pfefferbaum, Adolf (Psychopharmacology, 2014)
RATIONALE: Ventricular enlargement is a robust phenotype of the chronically dependent alcoholic human brain, yet the mechanism of ventriculomegaly is unestablished. Heterogeneous stock Wistar rats administered binge EtOH (3 g/kg intragastrically every 8 h for 4 days to average blood alcohol levels (BALs) of 250 mg/dL) demonstrate profound but reversible ventricular enlargement and changes in brain metabolites (e.g., N-acetylaspartate (NAA) and choline-containing compounds (Cho)). OBJECTIVES: Here, alcohol-preferring (P) and alcohol-nonpreferring (NP) rats systematically bred from heterogeneous stock Wistar rats for differential alcohol drinking behavior were compared with Wistar rats to determine whether genetic divergence and consequent morphological and neurochemical variation affect the brain's response to binge EtOH treatment. METHODS: The three rat lines were dosed equivalently and approached similar BALs. Magnetic resonance imaging and spectroscopy evaluated the effects of binge EtOH on brain. RESULTS: As observed in Wistar rats, P and NP rats showed decreases in NAA. Neither P nor NP rats, however, responded to EtOH intoxication with ventricular expansion or increases in Cho levels as previously noted in Wistar rats. Increases in ventricular volume correlated with increases in Cho in Wistar rats. CONCLUSIONS: The latter finding suggests that ventricular volume expansion is related to adaptive changes in brain cell membranes in response to binge EtOH. That P and NP rats responded differently to EtOH argues for intrinsic differences in their brain cell membrane composition. Further, differential metabolite responses to EtOH administration by rat strain implicate selective genetic variation as underlying heterogeneous effects of chronic alcoholism in the human condition.
Keywords: Animals; Aspartic Acid; Binge Drinking; Brain; Brain Chemistry; Cerebral Ventricles; Ethanol; Inbred Strains; Magnetic Resonance Imaging; Magnetic Resonance Spectroscopy; Male; Neuroimaging; Rats; Species Specificity; Wistar

Reduced ethanol consumption and preference in cocaine- and amphetamine-regulated transcript (CART) knockout mice - Salinas, Armando G.; Nguyen, Chinh T. Q.; Ahmadi-Tehrani, Dara; Morrisett, Richard A. (Addiction Biology, 2014)
Cocaine- and amphetamine-regulated transcript (CART) is a neuropeptide implicated in addiction to drugs of abuse. Several studies have characterized the role of CART in addiction to psychostimulants, but few have examined the role of CART in alcohol use disorders including alcoholism. The current study utilized a CART knockout (KO) mouse model to investigate the role of CART in ethanol appetitive behaviors. A two-bottle choice, unlimited-access paradigm was used to compare ethanol appetitive behaviors between CART wild type (WT) and KO mice. The mice were presented with an ethanol solution (3%-21%) and water, each concentration for 4 days, and their consumption was measured daily. Consumption of quinine (bitter) and saccharin (sweet) solutions was measured following the ethanol preference tests. In addition, ethanol metabolism rates and ethanol sensitivity were compared between genotypes. CART KO mice consumed and preferred ethanol less than their WT counterparts in both sexes. This genotype effect could not be attributed to differences in bitter or sweet taste perception or ethanol metabolism rates. There was also no difference in ethanol sensitivity in male mice; however, CART KO female mice showed a greater ethanol sensitivity than the WT females. Taken together, these data demonstrate a role for CART in ethanol appetitive behaviors and as a possible therapeutic drug target for alcoholism and abstinence enhancement.
Keywords: addiction; Alcohol Drinking; alcoholism; Analgesics; Animal; Animals; Appetitive Behavior; Brain; CART; Choice Behavior; Disease Models; Dose-Response Relationship; Drinking Water; Drug; Ethanol; Female; Food Preferences; Genotype; Genotyping Techniques; Immunohistochemistry; Knockout; Male; Mice; Mouse; Nerve Tissue Proteins; Non-Narcotic; Quinine; Reflex; Righting; Saccharin; Sex Characteristics; Sweetening Agents

Reinforcing properties and neurochemical response of ethanol within the posterior ventral tegmental area are enhanced in adulthood by periadolescent ethanol consumption - Toalston, Jamie E.; Deehan, Gerald A.; Hauser, Sheketha R.; Engleman, Eric A.; Bell, Richard L.; Murphy, James M.; Truitt, William A.; McBride, William J.; Rodd, Zachary A. (The Journal of Pharmacology and Experimental Therapeutics, 2014)
Alcohol drinking during adolescence is associated with increased alcohol drinking and alcohol dependence in adulthood. Research examining the biologic consequences of adolescent ethanol (EtOH) consumption on the response to EtOH in the neurocircuitry shown to regulate drug reinforcement is limited. The experiments were designed to determine the effects of periadolescent alcohol drinking on the reinforcing properties of EtOH within the posterior ventral tegmental area (pVTA) and the ability of EtOH microinjected into the pVTA to stimulate dopamine (DA) release in the nucleus accumbens shell (AcbSh). EtOH access (24-hour free-choice) by alcohol-preferring rats occurred during postnatal days (PND) 30-60. Animals were tested for their response to EtOH after PND 85. Intracranial self-administration techniques were performed to assess EtOH self-infusion into the pVTA. In the second experiment, rats received microinjections of EtOH into the pVTA, and dialysis samples were collected from the AcbSh. The results indicate that in rats that consumed EtOH during adolescence, the pVTA was more sensitive to the reinforcing effects of EtOH (a lower concentration of EtOH supported self-administration) and the ability of EtOH microinjected into the pVTA to stimulate DA release in the AcbSh was enhanced (sensitivity and magnitude). The data indicate that EtOH consumption during adolescence altered the mesolimbic DA system to be more sensitive and responsive to EtOH. This increase in the response to EtOH within the mesolimbic DA during adulthood could be part of biologic sequelae that are the basis for the deleterious effects of adolescent alcohol consumption on the rate of alcoholism during adulthood.
Keywords: Alcohol Drinking; Animals; dopamine; Ethanol; Male; Microinjections; Nucleus Accumbens; Rats; Reinforcement (Psychology); Self Administration; Ventral tegmental area

RNA-Seq reveals novel transcriptional reorganization in human alcoholic brain - Farris, Sean P.; Mayfield, R. Dayne (International Review of Neurobiology, 2014)
DNA microarrays have been used for over a decade to profile gene expression on a genomic scale. While this technology has advanced our understanding of complex cellular function, the reliance of microarrays on hybridization kinetics results in several technical limitations. For example, knowledge of the sequences being probed is required, distinguishing similar sequences is difficult because of cross-hybridization, and the relatively narrow dynamic range of the signal limits sensitivity. Recently, new technologies have been introduced that are based on novel sequencing methodologies. These next-generation sequencing methods do not have the limitations inherent to microarrays. Next-generation sequencing is unique since it allows the detection of all known and novel RNAs present in biological samples without bias toward known transcripts. In addition, the expression of coding and noncoding RNAs, alternative splicing events, and expressed single nucleotide polymorphisms (SNPs) can be identified in a single experiment. Furthermore, this technology allows for remarkably higher throughput while lowering sequencing costs. This significant shift in throughput and pricing makes low-cost access to whole genomes possible and more importantly expands sequencing applications far beyond traditional uses (Morozova & Marra, 2008) to include sequencing the transcriptome (RNA-Seq), providing detail on gene structure, alternative splicing events, expressed SNPs, and transcript size (Mane et al., 2009; Tang et al., 2009; Walter et al., 2009), in a single experiment, while also quantifying the absolute abundance of genes, all with greater sensitivity and dynamic range than the competing cDNA microarray technology (Mortazavi, Williams, McCue, Schaeffer, & Wold, 2008).
Keywords: Alcohol dependence; alcoholism; Brain; Genome; High-Throughput Nucleotide Sequencing; Humans; Postmortem brain tissue; RNA sequencing; RNA-seq; Transcriptome; Weighted Gene Coexpression Network Analysis

Rodent models of genetic contributions to motivation to abuse alcohol - Crabbe, John C. (Nebraska Symposium on Motivation. Nebraska Symposium on Motivation, 2014)
In summary, there are remarkably few studies focused on the genetic contributions to alcohol's reinforcing values. Almost all such studies examine the two-bottle preference test. Despite the deficiencies I have raised in its interpretation, a rodent genotype's willingness to drink ethanol when water is freely available offers a reasonable aggregate estimate of alcohol's reinforcing value relative to other genotypes (Green and Grahame 2008). As indicated above, however, preference drinking studies will likely never avoid the confounding role of taste preferences and most often yield intake levels not sufficient to yield a pharmacologically significant BAL. Thus, the quest for improved measures of reinforcing value continues. Of the potential motivational factors considered by McClearn in his seminal review in this series, we can safely conclude that rodent alcohol drinking is not primarily directed at obtaining calories. The role of taste (and odor) remains a challenge. McClearn appears to have been correct that especially those genotypes that avoid alcohol are probably doing so based on preingestive sensory cues; however, postingestive consequences are also important. Cunningham's intragastric model shows the role of both preingestional and postingestional modulating factors for the best known examples, the usually nearly absolutely alcohol-avoiding DBA/2J and HAP-2 mice. Much subsequent data reinforce McClearn's earlier conclusion that C57BL/6J mice, at least, do not regulate their intake around a given self-administered dose of alcohol by adjusting their intake. This leaves us with the puzzle of why nearly all genotypes, even those directionally selectively bred for high voluntary intake for many generations, fail to self-administer intoxicating amounts of alcohol. Since McClearn's review, many ingenious assays to index alcohol's motivational effects have been used extensively, and new methods for inducing dependence have supplanted the older ones prevalent in 1968. I have tried to identify promising areas where the power of genetics could be fruitfully harvested and generally feel that we have a much more clear idea now about some important experiments remaining to be performed.
Keywords: alcoholism; Animal; Animals; Behavior; Disease Models; Genetic Predisposition to Disease; Mice; Motivation; Rats

Scheduled access alcohol drinking by alcohol-preferring (P) and high-alcohol-drinking (HAD) rats: modeling adolescent and adult binge-like drinking - Bell, Richard L.; Rodd, Zachary A.; Engleman, Eric A.; Toalston, Jamie E.; McBride, William J. (Alcohol (Fayetteville, N.Y.), 2014)
Binge alcohol drinking continues to be a public health concern among today's youth and young adults. Moreover, an early onset of alcohol use, which usually takes the form of binge drinking, is associated with a greater risk for developing alcohol use disorders. Given this, it is important to examine this behavior in rat models of alcohol abuse and dependence. Toward that end, the objective of this article is to review findings on binge-like drinking by selectively bred alcohol-preferring (P) and high-alcohol-drinking (HAD) lines of rats. As reviewed elsewhere in this special issue, the P line meets all, and the HAD line meets most, of the proposed criteria for an animal model of alcoholism. One model of binge drinking is scheduled ethanol access during the dark cycle, which has been used by our laboratory for over 20 years. Our laboratory has also adopted a protocol involving the concurrent presentation of multiple ethanol concentrations. When this protocol is combined with limited access, ethanol intake is maximized yielding blood ethanol levels (BELs) in excess, sometimes greatly in excess, of 80 mg%. By extending these procedures to include multiple scheduled ethanol access sessions during the dark cycle for 5 consecutive days/week, P and HAD rats consume in 3 or 4 h as much as, if not more than, the amount usually consumed in a 24 h period. Under certain conditions, using the multiple scheduled access procedure, BELs exceeding 200 mg% can be achieved on a daily basis. An overview of findings from studies with other selectively bred, inbred, and outbred rats places these findings in the context of the existing literature. Overall, the findings support the use of P and HAD rats as animal models to study binge-like alcohol drinking and reveal that scheduled access procedures will significantly increase ethanol intake by other rat lines and strains as well.
Keywords: Adolescent; Adult; Alcohol Drinking; Animal; Animal model of alcoholism; Animals; Blood alcohol concentration; Choice Behavior; Discrete bout; Drinking-in-the-dark; Ethanol; Excessive intake; Extreme drinking; Female; Humans; Limited access; Loss-of-control drinking; Male; Models; Nocturnal drinking; Rats; Self Administration

Seeking structural specificity: direct modulation of pentameric ligand-gated ion channels by alcohols and general anesthetics - Howard, Rebecca J.; Trudell, James R.; Harris, R. Adron (Pharmacological Reviews, 2014)
Alcohols and other anesthetic agents dramatically alter neurologic function in a wide range of organisms, yet their molecular sites of action remain poorly characterized. Pentameric ligand-gated ion channels, long implicated in important direct effects of alcohol and anesthetic binding, have recently been illuminated in renewed detail thanks to the determination of atomic-resolution structures of several family members from lower organisms. These structures provide valuable models for understanding and developing anesthetic agents and for allosteric modulation in general. This review surveys progress in this field from function to structure and back again, outlining early evidence for relevant modulation of pentameric ligand-gated ion channels and the development of early structural models for ion channel function and modulation. We highlight insights and challenges provided by recent crystal structures and resulting simulations, as well as opportunities for translation of these newly detailed models back to behavior and therapy.
Keywords: Alcohol-Related Disorders; Alcohols; Anesthetics; Animal; Animals; Behavior; Binding Sites; Crystallography; Drug Design; General; Humans; Ligand-Gated Ion Channels; Ligands; Molecular Dynamics Simulation; Protein Binding; Protein Conformation; X-Ray

SLC30A10 is a cell surface-localized manganese efflux transporter, and parkinsonism-causing mutations block its intracellular trafficking and efflux activity - Leyva-Illades, Dinorah; Chen, Pan; Zogzas, Charles E.; Hutchens, Steven; Mercado, Jonathan M.; Swaim, Caleb D.; Morrisett, Richard A.; Bowman, Aaron B.; Aschner, Michael; Mukhopadhyay, Somshuvra (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2014)
Manganese (Mn) is an essential metal, but elevated cellular levels are toxic and may lead to the development of an irreversible parkinsonian-like syndrome that has no treatment. Mn-induced parkinsonism generally occurs as a result of exposure to elevated Mn levels in occupational or environmental settings. Additionally, patients with compromised liver function attributable to diseases, such as cirrhosis, fail to excrete Mn and may develop Mn-induced parkinsonism in the absence of exposure to elevated Mn. Recently, a new form of familial parkinsonism was reported to occur as a result of mutations in SLC30A10. The cellular function of SLC30A10 and the mechanisms by which mutations in this protein cause parkinsonism are unclear. Here, using a combination of mechanistic and functional studies in cell culture, Caenorhabditis elegans, and primary midbrain neurons, we show that SLC30A10 is a cell surface-localized Mn efflux transporter that reduces cellular Mn levels and protects against Mn-induced toxicity. Importantly, mutations in SLC30A10 that cause familial parkinsonism blocked the ability of the transporter to traffic to the cell surface and to mediate Mn efflux. Although expression of disease-causing SLC30A10 mutations were not deleterious by themselves, neurons and worms expressing these mutants exhibited enhanced sensitivity to Mn toxicity. Our results provide novel insights into the mechanisms involved in the onset of a familial form of parkinsonism and highlight the possibility of using enhanced Mn efflux as a therapeutic strategy for the potential management of Mn-induced parkinsonism, including that occurring as a result of mutations in SLC30A10.
Keywords: Animals; Caenorhabditis elegans; Cation Transport Proteins; Cell Membrane; Cells; Cultured; efflux; Female; GPP130; HeLa Cells; Humans; Inbred C57BL; Intracellular Fluid; Male; Manganese; Mice; Mutation; Parkinsonian Disorders; parkinsonism; Protein Transport; SLC30A10; trafficking

Synaptic adaptations by alcohol and drugs of abuse: changes in microRNA expression and mRNA regulation - Most, Dana; Workman, Emily; Harris, R. Adron (Frontiers in Molecular Neuroscience, 2014)
Local translation of mRNAs is a mechanism by which cells can rapidly remodel synaptic structure and function. There is ample evidence for a role of synaptic translation in the neuroadaptations resulting from chronic drug use and abuse. Persistent and coordinated changes of many mRNAs, globally and locally, may have a causal role in complex disorders such as addiction. In this review we examine the evidence that translational regulation by microRNAs drives synaptic remodeling and mRNA expression, which may regulate the transition from recreational to compulsive drug use. microRNAs are small, non-coding RNAs that control the translation of mRNAs in the cell and within spatially restricted sites such as the synapse. microRNAs typically repress the translation of mRNAs into protein by binding to the 3'UTR of their targets. As 'master regulators' of many mRNAs, changes in microRNAs could account for the systemic alterations in mRNA and protein expression observed with drug abuse and dependence. Recent studies indicate that manipulation of microRNAs affects addiction-related behaviors such as the rewarding properties of cocaine, cocaine-seeking behavior, and self-administration rates of alcohol. There is limited evidence, however, regarding how synaptic microRNAs control local mRNA translation during chronic drug exposure and how this contributes to the development of dependence. Here, we discuss research supporting microRNA regulation of local mRNA translation and how drugs of abuse may target this process. The ability of synaptic microRNAs to rapidly regulate mRNAs provides a discrete, localized system that could potentially be used as diagnostic and treatment tools for alcohol and other addiction disorders.
Keywords: Cocaine; Ethanol; miRNAs; mRNA targets; stimulants; synaptic translation; synaptoneurosomes

Use of animal models of alcohol-related behavior - Crabbe, John C. (Handbook of Clinical Neurology, 2014)
Alcoholism (alcohol dependence and alcohol use disorder, AUD) is quintessentially behavioral in nature. AUD is behaviorally and genetically complex. This review discusses behavioral assessment of alcohol sensitivity, tolerance, dependence, withdrawal, and reinforcement. The focus is on using laboratory animal models to explore genetic contributions to individual differences in alcohol responses. Rodent genetic animal models based on selective breeding for high vs low alcohol response, and those based on the use of inbred strains, are reviewed. Genetic strategies have revealed the complexity of alcohol responses where genetic influences on multiple alcohol-related behaviors are mostly discrete. They have also identified areas where genetic influences are consistent across behavioral assays and have been used to model genetic differences among humans at different risk for AUD.
Keywords: Alcohol-Related Disorders; alcoholism; Animal; Animals; Genetic Correlation; Genetics; Humans; Inbred Strains; Mice; Models; Mouse; rat; Rats; reinforcement; Reinforcement (Psychology); selected lines; sensitivity; Species Specificity; Tolerance; withdrawal

VTA CRF neurons mediate the aversive effects of nicotine withdrawal and promote intake escalation - Grieder, Taryn E.; Herman, Melissa A.; Contet, Candice; Tan, Laura A.; Vargas-Perez, Hector; Cohen, Ami; Chwalek, Michal; Maal-Bared, Geith; Freiling, John; Schlosburg, Joel E.; Clarke, Laura; Crawford, Elena; et al. (Nature Neuroscience, 2014)
Dopaminergic neurons in the ventral tegmental area (VTA) are well known for mediating the positive reinforcing effects of drugs of abuse. Here we identify in rodents and humans a population of VTA dopaminergic neurons expressing corticotropin-releasing factor (CRF). We provide further evidence in rodents that chronic nicotine exposure upregulates Crh mRNA (encoding CRF) in dopaminergic neurons of the posterior VTA, activates local CRF1 receptors and blocks nicotine-induced activation of transient GABAergic input to dopaminergic neurons. Local downregulation of Crh mRNA and specific pharmacological blockade of CRF1 receptors in the VTA reversed the effect of nicotine on GABAergic input to dopaminergic neurons, prevented the aversive effects of nicotine withdrawal and limited the escalation of nicotine intake. These results link the brain reward and stress systems in the same brain region to signaling of the negative motivational effects of nicotine withdrawal.
Keywords: Animals; Corticotropin-Releasing Hormone; Humans; Inbred C57BL; Inhibitory Postsynaptic Potentials; Male; Mice; Neurons; Nicotine; Organ Culture Techniques; Rats; Substance Withdrawal Syndrome; Ventral tegmental area; Wistar

White matter microstructural recovery with abstinence and decline with relapse in alcohol dependence interacts with normal ageing: a controlled longitudinal DTI study - Pfefferbaum, Adolf; Rosenbloom, Margaret J.; Chu, Weiwei; Sassoon, Stephanie A.; Rohlfing, Torsten; Pohl, Kilian M.; Zahr, Natalie M.; Sullivan, Edith V. (The Lancet. Psychiatry, 2014)
BACKGROUND: Alcohol dependence exacts a toll on brain white matter microstructure, which has the potential of repair with prolonged sobriety. Diffusion tensor imaging (DTI) enables in-vivo quantification of tissue constituents and localisation of tracts potentially affected in alcohol dependence and its recovery. We did an extended longitudinal study of alcoholism's trajectory of effect on selective fibre bundles with sustained sobriety or decline with relapse. METHODS: Participants were drawn from a longitudinal, 1·5T DTI database of 841 scans of individuals with various medical or neuropsychiatric conditions and normal ageing. Participants diagnosed with alcohol dependence had to meet the criteria from DSM-IV for alcohol dependence. Controls were screened and free of any DSM-IV axis I diagnosis, including being without history of alcohol or drug abuse or dependence. Tract-based spatial statistics (TBSS) quantified white matter integrity throughout the brain in 47 alcohol-dependent individuals and 56 controls examined 2-5 times over 1-8 year intervals. We identified regions showing group differences with a white matter atlas. For macrostructural comparison, we measured corpus callosum and centrum semiovale volumes on MRI. FINDINGS: This study took place in the USA, between June 23, 2000, and Sept 6, 2011. TBSS identified a large cluster (threshold p<0·001), where controls showed significant fractional anisotropy (FA) decrease with ageing and alcohol-dependent individuals had significantly lower FA than controls regardless of age. Over the examination interval, 27 (57%) alcohol-dependent individuals abstained, ten (21%) relapsed into light drinking, and ten (21%) relapsed into heavy drinking (>5 kg of alcohol/year). Despite abnormally low FA, age trajectories of the abstainers were positive and progressing toward normality, whereas those of the relapsers and controls were negative. Axial diffusivity (lower values indexing myelin integrity) was abnormally high in the total alcohol-dependent group; however, the abstainers' slopes paralleled those of controls, whereas the heavy-drinking relapsers' slopes showed accelerated ageing. Callosal genu and body microstructure but not macrostructure showed untoward alcohol-related effects. Affected projection and association tracts had an anterior and superior neuroanatomical distribution. INTERPRETATION: Return to heavy drinking resulted in accelerating microstructural white matter damage. Despite evidence for damage, alcohol-dependent individuals maintaining sobriety over extended periods showed improvement in brain fibre tract integrity reflective of fibre reorganisation and myelin restoration, indicative of a neural mechanism explaining recovery. FUNDING: US National Institute on Alcohol Abuse and Alcoholism (AA012388, AA017168, AA005965, AA013521-INIA).

BK channel β1 and β4 auxiliary subunits exert opposite influences on escalated ethanol drinking in dependent mice - Kreifeldt, Max; Le, David; Treistman, Steven N.; Koob, George F.; Contet, Candice (Frontiers in Integrative Neuroscience, 2013)
Large conductance calcium-activated potassium (BK) channels play a key role in the control of neuronal activity. Ethanol is a potent activator of BK channel gating, but how this action may impact ethanol drinking still remains poorly understood. Auxiliary β subunits are known to modulate ethanol-induced potentiation of BK currents. In the present study, we investigated whether BK β1 and β4 subunits influence voluntary ethanol consumption using knockout (KO) mice. In a first experiment, mice were first subjected to continuous two-bottle choice (2BC) and were then switched to intermittent 2BC, which progressively increased ethanol intake as previously described in wildtype mice. BK β1 or β4 subunit deficiency did not affect ethanol self-administration under either schedule of access. In a second experiment, mice were first trained to drink ethanol in a limited-access 2BC paradigm. BK β1 or β4 deletion did not affect baseline consumption. Weeks of 2BC were then alternated with weeks of chronic intermittent ethanol (CIE) or air inhalation. As expected, a gradual escalation of ethanol drinking was observed in dependent wildtype mice, while intake remained stable in non-dependent wildtype mice. However, CIE exposure only produced a mild augmentation of ethanol consumption in BK β4 KO mice. Conversely, ethanol drinking increased after fewer CIE cycles in BK β1 KO mice than in wildtype mice. In conclusion, BK β1 or β4 did not influence voluntary ethanol drinking in non-dependent mice, regardless of the pattern of access to ethanol. However, deletion of BK β4 attenuated, while deletion of BK β1 accelerated, the escalation of ethanol drinking during withdrawal from CIE. Our data suggest that BK β1 and β4 subunits have an opposite influence on the negative reinforcing properties of ethanol withdrawal. Modulating the expression, distribution or interactions of BK channel auxiliary subunits may therefore represent a novel avenue for the treatment of alcoholism.
Keywords: alcohol; dependence; Knockout mice; Two-bottle choice; vapor chambers

Caffeinated Alcoholic Beverages - An Emerging Trend in Alcohol Abuse - Franklin, Kelle M.; Hauser, Sheketha R.; Bell, Richard L.; Engleman, Eric A. (Journal of Addiction Research & Therapy, 2013)
Alcohol use disorders are pervasive in society and their impact affects quality of life, morbidity and mortality, as well as individual productivity. Alcohol has detrimental effects on an individual's physiology and nervous system, and is associated with disorders of many organ and endocrine systems impacting an individual's health, behavior, and ability to interact with others. Youth are particularly affected. Unfortunately, adolescent usage also increases the probability for a progression to dependence. Several areas of research indicate that the deleterious effects of alcohol abuse may be exacerbated by mixing caffeine with alcohol. Some behavioral evidence suggests that caffeine increases alcohol drinking and binge drinking episodes, which in turn can foster the development of alcohol dependence. As a relatively new public health concern, the epidemiological focus has been to establish a need for investigating the effects of caffeinated alcohol. While the trend of co-consuming these substances is growing, knowledge of the central mechanisms associated with caffeinated ethanol has been lacking. Research suggests that caffeine and ethanol can have additive or synergistic pharmacological actions and neuroadaptations, with the adenosine and dopamine systems in particular implicated. However, the limited literature on the central effects of caffeinated ethanol provides an impetus to increase our knowledge of the neuroadaptive effects of this combination and their impact on cognition and behavior. Research from our laboratories indicates that an established rodent animal model of alcoholism can be extended to investigate the acute and chronic effects of caffeinated ethanol.
Keywords: Adenosine; alcohol; Alcohol-preferring rat; Caffeinated alcohol; Caffeine; dopamine; Energy drink

Changes in gene expression within the ventral tegmental area following repeated excessive binge-like alcohol drinking by alcohol-preferring (P) rats - McBride, William J.; Kimpel, Mark W.; McClintick, Jeanette N.; Ding, Zheng-Ming; Hauser, Sheketha R.; Edenberg, Howard J.; Bell, Richard L.; Rodd, Zachary A. (Alcohol (Fayetteville, N.Y.), 2013)
The objective of this study was to detect changes in gene expression in the ventral tegmental area (VTA) following repeated excessive binge-like ('loss-of-control') alcohol drinking by alcohol-preferring (P) rats. Adult female P rats (n = 7) were given concurrent access to 10, 20, and 30% EtOH for 4 1-h sessions daily for 10 weeks followed by 2 cycles of 2 weeks of abstinence and 2 weeks of EtOH access. Rats were sacrificed by decapitation 3 h after the 4th daily EtOH-access session at the end of the second 2-week relapse period. A water-control group of female P rats (n = 8) was also sacrificed. RNA was prepared from micro-punch samples of the VTA from individual rats; analyses were conducted with Affymetrix Rat 230.2 GeneChips. Ethanol intakes were 1.2-1.7 g/kg per session, resulting in blood levels >200 mg% at the end of the 4th session. There were 211 unique named genes that significantly differed (FDR = 0.1) between the water and EtOH groups. Bioinformatics analyses indicated alterations in a) transcription factors that reduced excitation-coupled transcription and promoted excitotoxic neuronal damage involving clusters of genes associated with Nfkbia, Fos, and Srebf1, b) genes that reduced cholesterol and fatty acid synthesis, and increased protein degradation, and c) genes involved in cell-to-cell interactions and regulation of the actin cytoskeleton. Among the named genes, there were 62 genes that showed differences between alcohol-naïve P and non-preferring (NP) rats, with 43 of the genes changing toward NP-like expression levels following excessive binge-like drinking in the P rats. These genes are involved in a pro-inflammatory response, and enhanced response to glucocorticoids and steroid hormones. Overall, the results of this study indicate that the repeated excessive binge-like alcohol drinking can change the expression of genes that may alter neuronal function in several ways, some of which may be deleterious.
Keywords: alcoholism; Animals; Binge Drinking; Female; Gene Expression Regulation; Inbred Strains; Rats; Ventral tegmental area

Chronic voluntary alcohol consumption results in tolerance to sedative/hypnotic and hypothermic effects of alcohol in hybrid mice - Ozburn, Angela Renee; Harris, R. Adron; Blednov, Yuri A. (Pharmacology, Biochemistry, and Behavior, 2013)
The continuous two-bottle choice test is the most common measure of alcohol consumption but there is remarkably little information about the development of tolerance or dependence with this procedure. We showed that C57BL/6J × FVB/NJ and FVB/NJ×C57BL/6JF1 hybrid mice demonstrate greater preference for and consumption of alcohol than either parental strain. In order to test the ability of this genetic model of high alcohol consumption to produce neuroadaptation, we examined development of alcohol tolerance and dependence after chronic self-administration using a continuous access two-bottle choice paradigm. Ethanol-experienced mice stably consumed about 16-18 g/kg/day of ethanol. Ethanol-induced withdrawal severity was assessed (after 59 days of drinking) by scoring handling-induced convulsions; withdrawal severity was minimal and did not differ between ethanol-experienced and -naïve mice. After 71 days of drinking, the rate of ethanol clearance was similar for ethanol-experienced and -naïve mice. After 77 days of drinking, ethanol-induced loss of righting reflex (LORR) was tested daily for 5 days. Ethanol-experienced mice had a shorter duration of LORR. For both ethanol-experienced and -naïve mice, blood ethanol concentrations taken at gain of righting reflex were greater on day 5 than on day 1, indicative of tolerance. After 98 days of drinking, ethanol-induced hypothermia was assessed daily for 3 days. Both ethanol-experienced and -naïve mice developed rapid and chronic tolerance to ethanol-induced hypothermia, with significant group differences on the first day of testing. In summary, chronic, high levels of alcohol consumption in F1 hybrid mice produced rapid and chronic tolerance to both the sedative/hypnotic and hypothermic effects of ethanol; additionally, a small degree of metabolic tolerance developed. The development of tolerance supports the validity of using this model of high alcohol consumption in genetic studies of alcoholism.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Disease Models; Drug Tolerance; Ethanol; Female; Genetic; Hybridization; Hypnotics and Sedatives; Hypothermia; Inbred C57BL; Mice; Models; Reflex; Righting; Substance Withdrawal Syndrome

CRF1 receptor signaling regulates food and fluid intake in the drinking-in-the-dark model of binge alcohol consumption - Giardino, William J.; Ryabinin, Andrey E. (Alcoholism, Clinical and Experimental Research, 2013)
BACKGROUND: Several recent studies implementing the standard "drinking-in-the-dark" (DID) model of short-term binge-like ethanol (EtOH) intake in C57BL/6J mice highlighted a role for the stress-related neuropeptide corticotropin-releasing factor (CRF) and its primary binding partner, the CRF type-1 (CRF1) receptor. METHODS: We evaluated the selectivity of CRF1 involvement in binge-like EtOH intake by interrupting CRF1 function via pharmacological and genetic methods in a slightly modified 2-bottle choice DID model that allowed calculation of an EtOH preference ratio. In addition to determining EtOH intake and preference, we also measured consumption of food and H2 O during the DID period, both in the presence and absence of EtOH and sweet tastant solutions. RESULTS: Treatment with either of the CRF1-selective antagonists CP-376,395 (CP; 10 to 20 mg/kg, i.p.) or NBI-27914 (10 to 30 mg/kg, i.p.) decreased intake of 15% EtOH in male C57BL/6J mice, but did so in the absence of a concomitant decrease in EtOH preference. These findings were replicated genetically in a CRF1 knockout (KO) mouse model (also on a C57BL/6J background). In contrast to effects on EtOH intake, pharmacological blockade of CRF1 with CP increased intake of 10% sucrose, consistent with previous findings in CRF1 KO mice. Finally, pharmacological and genetic disruption of CRF1 activity significantly reduced feeding and/or total caloric intake in all experiments, confirming the existence of nonspecific effects. CONCLUSIONS: Our findings indicate that blockade of CRF1 receptors does not exert specific effects on EtOH intake in the DID paradigm, and that slight modifications to this procedure, as well as additional consummatory control experiments, may be useful when evaluating the selectivity of pharmacological and genetic manipulations on binge-like EtOH intake.
Keywords: alcohol; Alcohol Drinking; Aminopyridines; Aniline Compounds; Animal; Animals; Binge; Binge Drinking; Corticotropin; Corticotropin-Releasing Hormone; Darkness; Disease Models; Drinking; Eating; Female; Inbred C57BL; Knockout; Male; Mice; Pyrimidines; Receptors; Signal Transduction; Stress; urocortin

Delta opioid receptors in brain function and diseases - Chu Sin Chung, Paul; Kieffer, Brigitte L. (Pharmacology & Therapeutics, 2013)
Evidence that the delta opioid receptor (DOR) is an attractive target for the treatment of brain disorders has strengthened in recent years. This receptor is broadly expressed in the brain, binds endogenous opioid peptides, and shows as functional profile highly distinct from those of mu and kappa opioid receptors. Our knowledge of DOR function has enormously progressed from in vivo studies using pharmacological tools and genetic approaches. The important role of this receptor in reducing chronic pain has been extensively overviewed; therefore this review focuses on facets of delta receptor activity relevant to psychiatric and other neurological disorders. Beneficial effects of DOR agonists are now well established in the context of emotional responses and mood disorders. DOR activation also regulates drug reward, inhibitory controls and learning processes, but whether delta compounds may represent useful drugs in the treatment of drug abuse remains open. Epileptogenic and locomotor-stimulating effects of delta agonists appear drug-dependent, and the possibility of biased agonism at DOR for these effects is worthwhile further investigations to increase benefit/risk ratio of delta therapies. Neuroprotective effects of DOR activity represent a forthcoming research area. Future developments in DOR research will benefit from in-depth investigations of DOR function at cellular and circuit levels.
Keywords: Delta opioid receptor; In vivo; Knockout; Pathology; Pharmacology

Effects of ceftriaxone on the acquisition and maintenance of ethanol drinking in peri-adolescent and adult female alcohol-preferring (P) rats - Sari, Y.; Franklin, K. M.; Alazizi, A.; Rao, P. S. S.; Bell, R. L. (Neuroscience, 2013)
Increased glutamatergic neurotransmission appears to mediate the reinforcing properties of drugs of abuse, including ethanol (EtOH). We recently reported that the administration of ceftriaxone (CEF), a β-lactam antibiotic known to upregulate glutamate transporter 1 (GLT1) levels/activity, decreased the maintenance of EtOH intake in adult male alcohol-preferring (P) rats. In the present study, we tested whether CEF administration would reduce the acquisition and maintenance of EtOH drinking in adolescent and adult female P rats. The rats were treated with saline or 200mg/kg ceftriaxone for 7 days (starting at 35 or 75 days old, respectively) followed by the EtOH acquisition test. Five weeks later the effects of CEF were examined regarding the maintenance of EtOH intake. For the maintenance test, half of the animals that received CEF during acquisition received CEF for 7 days and the other half received saline for 7 days. Saline-treated acquisition animals were treated similarly. The results indicated that pretreatment with ceftriaxone reduced the maintenance of EtOH intake in both animals that started as adolescents and those that started as adults. However, the beneficial effect of CEF was more pronounced in rats pretreated with CEF as adults compared with rats pretreated as adolescents. Reductions in EtOH intake by ceftriaxone were paralleled by an upregulation of GLT1 protein levels in both the nucleus accumbens (∼25% in rats starting at both ages) and prefrontal cortex (∼50% in rats starting as peri-adolescents and ∼65% in those starting as adults). These findings provide further support for GLT1-associated mechanisms in high alcohol-consuming behavior, and hold promise for the development of effective treatments targeting alcohol abuse and dependence.
Keywords: Alcohol Drinking; alcoholism; Animals; Anti-Bacterial Agents; Blotting; Brain; Ceftriaxone; Female; Glucose Transporter Type 1; Rats; Western

Escalation of intake under intermittent ethanol access in diverse mouse genotypes - Rosenwasser, Alan M.; Fixaris, Michael C.; Crabbe, John C.; Brooks, Peter C.; Ascheid, Sonja (Addiction Biology, 2013)
Experimental animals offered continuous 24-hour free choice access to ethanol rarely display voluntary ethanol consumption at levels sufficient to induce intoxication or to engender dependence. One of the simplest ways to increase voluntary ethanol intake is to impose temporal limitations on ethanol availability. Escalation of ethanol intake has been observed in both rats and mice under a variety of different schedules of alternating ethanol access and deprivation. Although such effects have been observed in a variety of rat and mouse genotypes, little is known concerning possible genetic correlations between responses to intermittent ethanol access and other ethanol-related phenotypes. In the present study, we examined the effects of intermittent ethanol access in mouse genotypes characterized by divergent responses to ethanol in other domains, including ethanol preference (C57BL/6J and C3H/HeJ mice), binge-like ethanol drinking (High Drinking in the Dark and HS/Npt mice) and ethanol withdrawal severity (Withdrawal Seizure-Prone and Withdrawal Seizure-Resistant mice). Although intermittent ethanol access resulted in escalated ethanol intake in all tested genotypes, the robustness of the effect varied across genotypes. On the other hand, we saw no evidence that the effects of intermittent access are correlated with either binge-like drinking or withdrawal severity, and only weak evidence for a genetic correlation with baseline ethanol preference. Thus, these different ethanol-related traits appear to depend on largely unique sets of genetic mediators.
Keywords: Analysis of Variance; Animals; Binge Drinking; Central Nervous System Depressants; Ethanol; Genotype; Inbred C57BL; Male; Mice; Motor Activity; Substance Withdrawal Syndrome

Ethanol drinking in Withdrawal Seizure-Prone and -Resistant selected mouse lines - Crabbe, John C.; Spence, Stephanie E.; Huang, Lawrence C.; Cameron, Andy J.; Schlumbohm, Jason P.; Barkley-Levenson, Amanda M.; Metten, Pamela (Alcohol, 2013)
Withdrawal Seizure-Prone (WSP) and Withdrawal Seizure-Resistant (WSR) mouse lines were bidirectionally selectively bred, respectively, to have severe or mild ethanol withdrawal handling-induced convulsions (HICs) after cessation of 3 days of ethanol vapor inhalation. Murine genotypes with severe withdrawal have been found to show low ethanol consumption, and high consumers show low withdrawal. An early drinking study with WSP and WSR mice showed modest evidence consistent with this genetic correlation, but there were several limitations to that experiment. We therefore conducted a thorough assessment of two bottle ethanol preference drinking in both replicate pairs of WSP/WSR selected lines in mice of both sexes. Greater preference drinking of WSR-2 than WSP-2 female mice confirmed the earlier report. However, in the parallel set of selected lines, the WSP-1 mice drank more than the WSR-1s. Naive mice tested for preference for sucrose, saccharin and quinine did not differ markedly for any tastant. Finally, in a test of binge-like drinking, Drinking in the Dark (DID), WSP mice drank more than WSR mice and attained significantly higher (but still modest) blood ethanol concentrations. Tests of acute withdrawal after DID showed a mild, but significant elevation in handling-induced convulsions in the WSP line. These results provide further evidence that 2-bottle ethanol preference and DID are genetically distinguishable traits.
Keywords: Drinking in the dark; ethanol preference; Ethanol withdrawal; Genetics; Mouse; Selective breeding

Gene expression in brain and liver produced by three different regimens of alcohol consumption in mice: comparison with immune activation - Osterndorff-Kahanek, Elizabeth; Ponomarev, Igor; Blednov, Yuri A.; Harris, R. Adron (PloS One, 2013)
Chronically available alcohol escalates drinking in mice and a single injection of the immune activator lipopolysaccharide can mimic this effect and result in a persistent increase in alcohol consumption. We hypothesized that chronic alcohol drinking and lipopolysaccharide injections will produce some similar molecular changes that play a role in regulation of alcohol intake. We investigated the molecular mechanisms of chronic alcohol consumption or lipopolysaccharide insult by gene expression profiling in prefrontal cortex and liver of C57BL/6J mice. We identified similar patterns of transcriptional changes among four groups of animals, three consuming alcohol (vs water) in different consumption tests and one injected with lipopolysaccharide (vs. vehicle). The three tests of alcohol consumption are the continuous chronic two bottle choice (Chronic), two bottle choice available every other day (Chronic Intermittent) and limited access to one bottle of ethanol (Drinking in the Dark). Gene expression changes were more numerous and marked in liver than in prefrontal cortex for the alcohol treatments and similar in the two tissues for lipopolysaccharide. Many of the changes were unique to each treatment, but there was significant overlap in prefrontal cortex for Chronic-Chronic Intermittent and for Chronic Intermittent-lipopolysaccharide and in liver all pairs showed overlap. In silico cell-type analysis indicated that lipopolysaccharide had strongest effects on brain microglia and liver Kupffer cells. Pathway analysis detected a prefrontal cortex-based dopamine-related (PPP1R1B, DRD1, DRD2, FOSB, PDNY) network that was highly over-represented in the Chronic Intermittent group, with several genes from the network being also regulated in the Chronic and lipopolysaccharide (but not Drinking in the Dark) groups. Liver showed a CYP and GST centered metabolic network shared in part by all four treatments. We demonstrate common consequences of chronic alcohol consumption and immune activation in both liver and brain and show distinct genomic consequences of different types of alcohol consumption.
Keywords: Alcohol Drinking; Animals; Brain; Choice Behavior; Drinking Behavior; Ethanol; Female; Gene Expression Profiling; Gene Expression Regulation; Inbred C57BL; Lipopolysaccharides; Liver; Mice; Prefrontal Cortex; Signal Transduction

Gene expression within the extended amygdala of 5 pairs of rat lines selectively bred for high or low ethanol consumption - McBride, William J.; Kimpel, Mark W.; McClintick, Jeanette N.; Ding, Zheng-Ming; Hyytia, Petri; Colombo, Giancarlo; Liang, Tiebing; Edenberg, Howard J.; Lumeng, Lawrence; Bell, Richard L. (Alcohol (Fayetteville, N.Y.), 2013)
The objectives of this study were to determine innate differences in gene expression in 2 regions of the extended amygdala between 5 different pairs of lines of male rats selectively bred for high or low ethanol consumption: a) alcohol-preferring (P) vs. alcohol-non-preferring (NP) rats, b) high-alcohol-drinking (HAD) vs. low-alcohol-drinking (LAD) rats (replicate line-pairs 1 and 2), c) ALKO alcohol (AA) vs. nonalcohol (ANA) rats, and d) Sardinian alcohol-preferring (sP) vs. Sardinian alcohol-nonpreferring (sNP) rats, and then to determine if these differences are common across the line-pairs. Microarray analysis revealed up to 1772 unique named genes in the nucleus accumbens shell (AcbSh) and 494 unique named genes in the central nucleus of the amygdala (CeA) that significantly differed [False Discovery Rate (FDR) = 0.10; fold-change at least 1.2] in expression between the individual line-pairs. Analysis using Gene Ontology (GO) and Ingenuity Pathways information indicated significant categories and networks in common for up to 3 or 4 line-pairs, but not for all 5 line-pairs. However, there were almost no individual genes in common within these categories and networks. ANOVAs of the combined data for the 5 line-pairs indicated 1014 and 731 significant (p < 0.01) differences in expression of named genes in the AcbSh and CeA, respectively. There were 4-6 individual named genes that significantly differed across up to 3 line-pairs in both regions; only 1 gene (Gsta4 in the CeA) differed in as many as 4 line-pairs. Overall, the findings suggest that a) some biological categories or networks (e.g., cell-to-cell signaling, cellular stress response, cellular organization, etc.) may be in common for subsets of line-pairs within either the AcbSh or CeA, and b) regulation of different genes and/or combinations of multiple biological systems may be contributing to the disparate alcohol drinking behaviors of these line-pairs.
Keywords: Alcohol Drinking; Alcohol-preferring; Alko alcohol; Amygdala; Animals; Breeding; Central nucleus of the amygdala; Ethanol; Gene Expression; Gene Ontology; High-alcohol-drinking; Male; Nucleus Accumbens; Principal Component Analysis; Rats; Sardinian alcohol-preferring; Selectively bred rat lines; Signal Transduction; Transcriptome

Genes, behavior and next-generation RNA sequencing - Hitzemann, R.; Bottomly, D.; Darakjian, P.; Walter, N.; Iancu, O.; Searles, R.; Wilmot, B.; McWeeney, S. (Genes, Brain, and Behavior, 2013)
Advances in next-generation sequencing suggest that RNA-Seq is poised to supplant microarray-based approaches for transcriptome analysis. This article briefly reviews the use of microarrays in the brain-behavior context and then illustrates why RNA-Seq is a superior strategy. Compared with microarrays, RNA-Seq has a greater dynamic range, detects both coding and noncoding RNAs, is superior for gene network construction, detects alternative spliced transcripts, detects allele specific expression and can be used to extract genotype information, e.g. nonsynonymous coding single nucleotide polymorphisms. Examples of where RNA-Seq has been used to assess brain gene expression are provided. Despite the advantages of RNA-Seq, some disadvantages remain. These include the high cost of RNA-Seq and the computational complexities associated with data analysis. RNA-Seq embraces the complexity of the transcriptome and provides a mechanism to understand the underlying regulatory code; the potential to inform the brain-behavior relationship is substantial.
Keywords: Animals; Brain; Gene Expression Profiling; Genes; High-Throughput Nucleotide Sequencing; Humans; Oligonucleotide Array Sequence Analysis; RNA; Sequence Analysis

Genetic markers of comorbid depression and alcoholism in women - Procopio, Daniela O.; Saba, Laura M.; Walter, Henriette; Lesch, Otto; Skala, Katrin; Schlaff, Golda; Vanderlinden, Lauren; Clapp, Peter; Hoffman, Paula L.; Tabakoff, Boris (Alcoholism, Clinical and Experimental Research, 2013)
BACKGROUND: Alcohol dependence (AD) is often accompanied by comorbid depression. Recent clinical evidence supports the benefit of subtype-specific pharmacotherapy in treating the population of alcohol-dependent subjects with comorbid major depressive disorder (MDD). However, in many alcohol-dependent subjects, depression is a reactive response to chronic alcohol use and withdrawal and abates with a period of abstinence. Genetic markers may distinguish alcohol-dependent subjects with MDD not tied chronologically and etiologically to their alcohol consumption. In this work, we investigated the association of adenylyl cyclase genes (ADCY1-9), which are implicated in both AD and mood disorders, with alcoholism and comorbid depression. METHODS: Subjects from Vienna, Austria (n = 323) were genotyped, and single nucleotide polymorphisms (1,152) encompassing the genetic locations of the 9 ADCY genes were examined. The Vienna cohort contained alcohol-dependent subjects differentiated using the Lesch Alcoholism Typology. In this typology, subjects are segregated into 4 types. Type III alcoholism is distinguished by co-occurrence of symptoms of depression and by affecting predominantly females. RESULTS: We identified 4 haplotypes associated with the phenotype of Type III alcoholism in females. One haplotype was in a genomic area in proximity to ADCY2, but actually within a lincRNA gene, 2 haplotypes were within ADCY5, and 1 haplotype was within the coding region of ADCY8. Three of the 4 haplotypes contributed independently to Type III alcoholism and together generated a positive predictive value of 72% and a negative predictive value of 78% for distinguishing women with a Lesch Type III diagnosis versus women designated as Type I or II alcoholics. CONCLUSIONS: Polymorphisms in ADCY8 and ADCY5 and within a lincRNA are associated with an alcohol-dependent phenotype in females, which is distinguished by comorbid signs of depression. Each of these genetic locations can rationally contribute to the polygenic etiology of the alcoholism/depression phenotype, and the use of these genetic markers may aid in choosing appropriate and beneficial treatment strategies.
Keywords: Adenylyl Cyclases; alcoholism; Depressive Disorder; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Long Noncoding; Major; Male; Polymorphism; RNA; Single Nucleotide

Genetics and alcoholism - Edenberg, Howard J.; Foroud, Tatiana (Nature Reviews. Gastroenterology & Hepatology, 2013)
Alcohol is widely consumed; however, excessive use creates serious physical, psychological and social problems and contributes to the pathogenesis of many diseases. Alcohol use disorders (that is, alcohol dependence and alcohol abuse) are maladaptive patterns of excessive drinking that lead to serious problems. Abundant evidence indicates that alcohol dependence (alcoholism) is a complex genetic disease, with variations in a large number of genes affecting a person's risk of alcoholism. Some of these genes have been identified, including two genes involved in the metabolism of alcohol (ADH1B and ALDH2) that have the strongest known affects on the risk of alcoholism. Studies continue to reveal other genes in which variants affect the risk of alcoholism or related traits, including GABRA2, CHRM2, KCNJ6 and AUTS2. As more variants are analysed and studies are combined for meta-analysis to achieve increased sample sizes, an improved picture of the many genes and pathways that affect the risk of alcoholism will be possible.
Keywords: Alcohol Dehydrogenase; alcoholism; Aldehyde Dehydrogenase; G Protein-Coupled Inwardly-Rectifying Potassium Channels; GABA-A; Humans; Liver; Mitochondrial; Muscarinic M2; Proteins; Receptor; Receptors; Risk Factors

Ghrelin increases GABAergic transmission and interacts with ethanol actions in the rat central nucleus of the amygdala - Cruz, Maureen T.; Herman, Melissa A.; Cote, Dawn M.; Ryabinin, Andrey E.; Roberto, Marisa (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2013)
The neural circuitry that processes natural rewards converges with that engaged by addictive drugs. Because of this common neurocircuitry, drugs of abuse have been able to engage the hedonic mechanisms normally associated with the processing of natural rewards. Ghrelin is an orexigenic peptide that stimulates food intake by activating GHS-R1A receptors in the hypothalamus. However, ghrelin also activates GHS-R1A receptors on extrahypothalamic targets that mediate alcohol reward. The central nucleus of the amygdala (CeA) has a critical role in regulating ethanol consumption and the response to ethanol withdrawal. We previously demonstrated that rat CeA GABAergic transmission is enhanced by acute and chronic ethanol treatment. Here, we used quantitative RT-PCR (qRT-PCR) to detect Ghsr mRNA in the CeA and performed electrophysiological recordings to measure ghrelin effects on GABA transmission in this brain region. Furthermore, we examined whether acute or chronic ethanol treatment would alter these electrophysiological effects. Our qRT-PCR studies show the presence of Ghsr mRNA in the CeA. In naive animals, superfusion of ghrelin increased the amplitude of evoked inhibitory postsynaptic potentials (IPSPs) and the frequency of miniature inhibitory postsynaptic currents (mIPSCs). Coapplication of ethanol further increased the ghrelin-induced enhancement of IPSP amplitude, but to a lesser extent than ethanol alone. When applied alone, ethanol significantly increased IPSP amplitude, but this effect was attenuated by the application of ghrelin. In neurons from chronic ethanol-treated (CET) animals, the magnitude of ghrelin-induced increases in IPSP amplitude was not significantly different from that in naive animals, but the ethanol-induced increase in amplitude was abolished. Superfusion of the GHS-R1A antagonists D-Lys3-GHRP-6 and JMV 3002 decreased evoked IPSP and mIPSC frequency, revealing tonic ghrelin activity in the CeA. D-Lys3-GHRP-6 and JMV 3002 also blocked ghrelin-induced increases in GABAergic responses. Furthermore, D-Lys3-GHRP-6 did not affect ethanol-induced increases in IPSP amplitude. These studies implicate a potential role for the ghrelin system in regulating GABAergic transmission and a complex interaction with ethanol at CeA GABAergic synapses.
Keywords: Administration; Amygdala; Animals; Ethanol; GABAergic Neurons; Ghrelin; Inhalation; Inhibitory Postsynaptic Potentials; Male; Organ Culture Techniques; Rats; Sprague-Dawley; Synaptic Transmission

A history of chronic morphine exposure during adolescence increases despair-like behaviour and strain-dependently promotes sociability in abstinent adult mice - Lutz, P. E.; Reiss, D.; Ouagazzal, A. M.; Kieffer, B. L. (Behavioural Brain Research, 2013)
A crucial issue in treating opiate addiction, a chronic relapsing disorder, is to maintain a drug-free abstinent state. Prolonged abstinence associates with mood disorders, strongly contributing to relapse. In particular, substance use disorders occurring during adolescence predispose to depression later in adulthood. Using our established mouse model of opiate abstinence, we characterized emotional consequences into adulthood of morphine exposure during adolescence. Our results indicate that morphine treatment in adolescent mice has no effect on anxiety-like behaviours in adult mice, after abstinence. In contrast, morphine treatment during adolescence increases behavioural despair in adult mice. We also show that morphine exposure strain-dependently enhances sociability in adult mice. Additional research will be required to understand where and how morphine acts during brain maturation to affect emotional and social behaviours into adulthood.
Keywords: Aging; Animal; Animals; Anxiety; Behavior; Chronic Disease; Disease Models; Emotions; Inbred BALB C; Inbred C57BL; Male; Mice; Morphine; Morphine Dependence; Narcotics; Neuropsychological Tests; Social Behavior; Substance Withdrawal Syndrome

Impaired hippocampus-dependent and facilitated striatum-dependent behaviors in mice lacking the δ opioid receptor - Le Merrer, Julie; Rezai, Xavier; Scherrer, Grégory; Becker, Jérôme A. J.; Kieffer, Brigitte L. (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2013)
Pharmacological data suggest that delta opioid receptors modulate learning and memory processes. In the present study, we investigated whether inactivation of the delta opioid receptor modifies hippocampus (HPC)- and striatum-dependent behaviors. We first assessed HPC-dependent learning in mice lacking the receptor (Oprd1(-/-) mice) or wild-type (WT) mice treated with the delta opioid antagonist naltrindole using novel object recognition, and a dual-solution cross-maze task. Second, we subjected mutant animals to memory tests addressing striatum-dependent learning using a single-solution response cross-maze task and a motor skill-learning task. Genetic and pharmacological inactivation of delta opioid receptors reduced performance in HPC-dependent object place recognition. Place learning was also altered in Oprd1(-/-) animals, whereas striatum-dependent response and procedural learning were facilitated. Third, we investigated the expression levels for a large set of genes involved in neurotransmission in both HPC and striatum of Oprd1(-/-) mice. Gene expression was modified for several key genes that may contribute to alter hippocampal and striatal functions, and bias striatal output towards striatonigral activity. To test this hypothesis, we finally examined locomotor effects of dopamine receptor agonists. We found that Oprd1(-/-) and naltrindole-treated WT mice were more sensitive to the stimulant locomotor effect of SKF-81297 (D1/D5), supporting the hypothesis of facilitated striatonigral output. These data suggest, for the first time, that delta receptor activity tonically inhibits striatal function, and demonstrate that delta opioid receptors modulate learning and memory performance by regulating the HPC/striatum balance.
Keywords: 129 Strain; Animals; Corpus Striatum; delta; Hippocampus; Humans; Inbred C57BL; Knockout; Male; Memory; Mice; Motor Activity; Motor Skills; Opioid; Receptors

Integration of miRNA and protein profiling reveals coordinated neuroadaptations in the alcohol-dependent mouse brain - Gorini, Giorgio; Nunez, Yury O.; Mayfield, R. Dayne (PloS One, 2013)
The molecular mechanisms underlying alcohol dependence involve different neurochemical systems and are brain region-dependent. Chronic Intermittent Ethanol (CIE) procedure, combined with a Two-Bottle Choice voluntary drinking paradigm, represents one of the best available animal models for alcohol dependence and relapse drinking. MicroRNAs, master regulators of the cellular transcriptome and proteome, can regulate their targets in a cooperative, combinatorial fashion, ensuring fine tuning and control over a large number of cellular functions. We analyzed cortex and midbrain microRNA expression levels using an integrative approach to combine and relate data to previous protein profiling from the same CIE-subjected samples, and examined the significance of the data in terms of relative contribution to alcohol consumption and dependence. MicroRNA levels were significantly altered in CIE-exposed dependent mice compared with their non-dependent controls. More importantly, our integrative analysis identified modules of coexpressed microRNAs that were highly correlated with CIE effects and predicted target genes encoding differentially expressed proteins. Coexpressed CIE-relevant proteins, in turn, were often negatively correlated with specific microRNA modules. Our results provide evidence that microRNA-orchestrated translational imbalances are driving the behavioral transition from alcohol consumption to dependence. This study represents the first attempt to combine ex vivo microRNA and protein expression on a global scale from the same mammalian brain samples. The integrative systems approach used here will improve our understanding of brain adaptive changes in response to drug abuse and suggests the potential therapeutic use of microRNAs as tools to prevent or compensate multiple neuroadaptations underlying addictive behavior.
Keywords: Adaptation; alcoholism; Animals; Brain; Ethanol; Gene Expression Profiling; Gene Regulatory Networks; Inbred C57BL; Male; Mice; MicroRNAs; Neurons; Physiological; Proteome; Systems Integration; Transcriptome

Linking GABA(A) receptor subunits to alcohol-induced conditioned taste aversion and recovery from acute alcohol intoxication - Blednov, Y. A.; Benavidez, J. M.; Black, M.; Chandra, D.; Homanics, G. E.; Rudolph, U.; Harris, R. A. (Neuropharmacology, 2013)
GABA type A receptors (GABA(A)-R) are important for ethanol actions and it is of interest to link individual subunits with specific ethanol behaviors. We studied null mutant mice for six different GABA(A)-R subunits (α1, α2, α3, α4, α5 and δ). Only mice lacking the α2 subunit showed reduction of conditioned taste aversion (CTA) to ethanol. These results are in agreement with data from knock-in mice with mutation of the ethanol-sensitive site in the α2-subunit (Blednov et al., 2011). All together, they indicate that aversive property of ethanol is dependent on ethanol action on α2-containing GABA(A)-R. Deletion of the α2-subunit led to faster recovery whereas absence of the α3-subunit slowed recovery from ethanol-induced incoordination (rotarod). Deletion of the other four subunits did not affect this behavior. Similar changes in this behavior for the α2 and α3 null mutants were found for flurazepam motor incoordination. However, no differences in recovery were found in motor-incoordinating effects of an α1-selective modulator (zolpidem) or an α4-selective agonist (gaboxadol). Therefore, recovery of rotarod incoordination is under control of two GABA(A)-R subunits: α2 and α3. For motor activity, α3 null mice demonstrated higher activation by ethanol (1 g/kg) whereas both α2 (-/-) and α3 (-/Y) knockout mice were less sensitive to ethanol-induced reduction of motor activity (1.5 g/kg). These studies demonstrate that the effects of ethanol at GABAergic synapses containing α2 subunit are important for specific behavioral effects of ethanol which may be relevant to the genetic linkage of the α2 subunit with human alcoholism.
Keywords: Acute Disease; Alcoholic Intoxication; Animals; Avoidance Learning; Ethanol; GABA-A; Genetic Linkage; Inbred C57BL; Knockout; Male; Mice; Receptors; Recovery of Function; Taste

Local changes in neurosteroid levels in the substantia nigra reticulata and the ventral tegmental area alter chronic ethanol withdrawal severity in male withdrawal seizure-prone mice - Tanchuck, Michelle A.; Cozzoli, Debra K.; He, Ingrid; Kaufman, Katherine R.; Snelling, Christopher; Crabbe, John C.; Mark, Gregory P.; Finn, Deborah A. (Alcoholism, Clinical and Experimental Research, 2013)
BACKGROUND: Allopregnanolone (ALLO) is a potent positive modulator of γ-aminobutyric acidA receptors (GABAA Rs) that affects ethanol (EtOH) withdrawal. Finasteride (FIN), a 5α-reductase inhibitor that blocks the formation of ALLO and other GABAergic neurosteroids, alters EtOH sensitivity. Recently, we found that Withdrawal Seizure-Prone mice from the first genetic replicate (WSP-1) exhibited behavioral tolerance to the anticonvulsant effect of intrahippocampal ALLO during EtOH withdrawal and that intrahippocampal FIN significantly increased EtOH withdrawal severity. The purpose of this study was to determine whether neurosteroid manipulations in the substantia nigra reticulata (SNR) and ventral tegmental area (VTA) produced effects during EtOH withdrawal comparable to those seen with intrahippocampal ALLO and FIN. METHODS: Male WSP-1 mice were surgically implanted with bilateral guide cannulae aimed at the SNR or VTA at 2 weeks prior to EtOH vapor or air exposure for 72 hours. Initial studies examined the anticonvulsant effect of a single ALLO infusion (0, 100, or 400 ng/side) at a time corresponding to peak withdrawal in the air- and EtOH-exposed mice. Separate studies examined the effect of 4 FIN infusions (0 or 10 μg/side/d) during the development of physical dependence on the expression of EtOH withdrawal. RESULTS: ALLO infusion exerted a potent anticonvulsant effect in EtOH-naïve mice, but a diminished anticonvulsant effect during EtOH withdrawal. Administration of FIN into the SNR exerted a delayed proconvulsant effect in EtOH-naïve mice, whereas infusion into the VTA increased EtOH withdrawal duration. CONCLUSIONS: Activation of local GABAA Rs in the SNR and VTA via ALLO infusion is sufficient to exert an anticonvulsant effect in naïve mice and to produce behavioral tolerance to the anticonvulsant effect of ALLO infusion during EtOH withdrawal. Thus, EtOH withdrawal reduced sensitivity of GABAA Rs to GABAergic neurosteroids in 2 neuroanatomical substrates within the basal ganglia in WSP-1 male mice.
Keywords: 5-alpha Reductase Inhibitors; Alcohol Withdrawal Seizures; Animals; Anticonvulsants; Central Nervous System Depressants; Ethanol; Finasteride; GABA Agents; GABA-A; Male; Mice; Microinjections; Pregnanolone; Receptors; Severity of Illness Index; Substantia Nigra; Ventral tegmental area

Modeling the diagnostic criteria for alcohol dependence with genetic animal models - Crabbe, John C.; Kendler, Kenneth S.; Hitzemann, Robert J. (Current Topics in Behavioral Neurosciences, 2013)
A diagnosis of alcohol dependence (AD) using the DSM-IV-R is categorical, based on an individual's manifestation of three or more symptoms from a list of seven. AD risk can be traced to both genetic and environmental sources. Most genetic studies of AD risk implicitly assume that an AD diagnosis represents a single underlying genetic factor. We recently found that the criteria for an AD diagnosis represent three somewhat distinct genetic paths to individual risk. Specifically, heavy use and tolerance versus withdrawal and continued use despite problems reflected separate genetic factors. However, some data suggest that genetic risk for AD is adequately described with a single underlying genetic risk factor. Rodent animal models for alcohol-related phenotypes typically target discrete aspects of the complex human AD diagnosis. Here, we review the literature derived from genetic animal models in an attempt to determine whether they support a single-factor or multiple-factor genetic structure. We conclude that there is modest support in the animal literature that alcohol tolerance and withdrawal reflect distinct genetic risk factors, in agreement with our human data. We suggest areas where more research could clarify this attempt to align the rodent and human data.
Keywords: Alcohol-Related Disorders; Animal; Animals; Disease Models; Genetic Predisposition to Disease; Humans

The multiple facets of opioid receptor function: implications for addiction - Lutz, Pierre-Eric; Kieffer, Brigitte L. (Current Opinion in Neurobiology, 2013)
Addiction is characterized by altered reward processing, disrupted emotional responses and poor decision-making. Beyond a central role in drug reward, increasing evidence indicate that opioid receptors are broadly involved in all these processes. Recent studies establish the mu opioid receptor as a main player in social reward, which attracts increasing attention in psychiatric research. There is growing interest in blocking the kappa opioid receptor to prevent relapse, and alleviate the negative affect of withdrawal. The delta opioid receptor emerges as a potent mood enhancer, whose involvement in addiction is less clear. All three opioid receptors are likely implicated in addiction-depression comorbidity, and understanding of their roles in cognitive deficits associated to drug abuse is only beginning.
Keywords: Animals; Brain; Humans; Opioid; Receptors; Reward; Substance-Related Disorders

Mutation of a zinc-binding residue in the glycine receptor α1 subunit changes ethanol sensitivity in vitro and alcohol consumption in vivo - McCracken, Lindsay M.; Blednov, Yuri A.; Trudell, James R.; Benavidez, Jillian M.; Betz, Heinrich; Harris, R. Adron (The Journal of Pharmacology and Experimental Therapeutics, 2013)
Ethanol is a widely used drug, yet an understanding of its sites and mechanisms of action remains incomplete. Among the protein targets of ethanol are glycine receptors (GlyRs), which are potentiated by millimolar concentrations of ethanol. In addition, zinc ions also modulate GlyR function, and recent evidence suggests that physiologic concentrations of zinc enhance ethanol potentiation of GlyRs. Here, we first built a homology model of a zinc-bound GlyR using the D80 position as a coordination site for a zinc ion. Next, we investigated in vitro the effects of zinc on ethanol action at recombinant wild-type (WT) and mutant α1 GlyRs containing the D80A substitution, which eliminates zinc potentiation. At D80A GlyRs, the effects of 50 and 200 mM ethanol were reduced as compared with WT receptors. Also, in contrast to what was seen with WT GlyRs, neither adding nor chelating zinc changed the magnitude of ethanol enhancement of mutant D80A receptors. Next, we evaluated the in vivo effects of the D80A substitution by using heterozygous Glra1(D80A) knock-in (KI) mice. The KI mice showed decreased ethanol consumption and preference, and they displayed increased startle responses compared with their WT littermates. Other behavioral tests, including ethanol-induced motor incoordination and strychnine-induced convulsions, revealed no differences between the KI and WT mice. Together, our findings indicate that zinc is critical in determining the effects of ethanol at GlyRs and suggest that zinc binding at the D80 position may be important for mediating some of the behavioral effects of ethanol action at GlyRs.
Keywords: Acoustic Stimulation; Alcohol Drinking; Amino Acid Substitution; Animal; Animals; Behavior; Binding Sites; Electrophysiological Phenomena; Ethanol; Female; Gene Knock-In Techniques; Glycine; Homozygote; Male; Mice; Models; Molecular; Mutagenesis; Mutant Strains; Oocytes; Point Mutation; Receptors; Reflex; Righting; Rotarod Performance Test; Site-Directed; Startle; strychnine; Transfection; Xenopus laevis; Zinc

Neurobiological signatures of alcohol dependence revealed by protein profiling - Gorini, Giorgio; Roberts, Amanda J.; Mayfield, R. Dayne (PloS One, 2013)
Alcohol abuse causes dramatic neuroadaptations in the brain, which contribute to tolerance, dependence, and behavioral modifications. Previous proteomic studies in human alcoholics and animal models have identified candidate alcoholism-related proteins. However, recent evidences suggest that alcohol dependence is caused by changes in co-regulation that are invisible to single protein-based analysis. Here, we analyze global proteomics data to integrate differential expression, co-expression networks, and gene annotations to unveil key neurobiological rearrangements associated with the transition to alcohol dependence modeled by a Chronic Intermittent Ethanol (CIE), two-bottle choice (2BC) paradigm. We analyzed cerebral cortices (CTX) and midbrains (MB) from male C57BL/6J mice subjected to a CIE, 2BC paradigm, which induces heavy drinking and represents one of the best available animal models for alcohol dependence and relapse drinking. CIE induced significant changes in protein levels in dependent mice compared with their non-dependent controls. Multiple protein isoforms showed region-specific differential regulation as a result of post-translational modifications. Our integrative analysis identified modules of co-expressed proteins that were highly correlated with CIE treatment. We found that modules most related to the effects of CIE treatment coordinate molecular imbalances in endocytic- and energy-related pathways, with specific proteins involved, such as dynamin-1. The qRT-PCR experiments validated both differential and co-expression analyses, and the correspondence among our data and previous genomic and proteomic studies in humans and rodents substantiates our findings. The changes identified above may play a key role in the escalation of ethanol consumption associated with dependence. Our approach to alcohol addiction will advance knowledge of brain remodeling mechanisms and adaptive changes in response to drug abuse, contribute to understanding of organizational principles of CTX and MB proteomes, and define potential new molecular targets for treating alcohol addiction. The integrative analysis employed here highlight the advantages of systems approaches in studying the neurobiology of alcohol addiction.
Keywords: Alcohol Drinking; alcoholism; Animals; Brain; Choice Behavior; Drinking Behavior; Ethanol; Immunoelectrophoresis; Inbred C57BL; Male; Matched-Pair Analysis; Mice; Proteome; Transcriptome; Two-Dimensional

The neurobiology of alcohol consumption and alcoholism: an integrative history - Tabakoff, Boris; Hoffman, Paula L. (Pharmacology, Biochemistry, and Behavior, 2013)
Studies of the neurobiological predisposition to consume alcohol (ethanol) and to transition to uncontrolled drinking behavior (alcoholism), as well as studies of the effects of alcohol on brain function, started a logarithmic growth phase after the repeal of the 18th Amendment to the United States Constitution. Although the early studies were primitive by current technological standards, they clearly demonstrated the effects of alcohol on brain structure and function, and by the end of the 20th century left little doubt that alcoholism is a "disease" of the brain. This review traces the history of developments in the understanding of ethanol's effects on the most prominent inhibitory and excitatory systems of brain (GABA and glutamate neurotransmission). This neurobiological information is integrated with knowledge of ethanol's actions on other neurotransmitter systems to produce an anatomical and functional map of ethanol's properties. Our intent is limited in scope, but is meant to provide context and integration of the actions of ethanol on the major neurobiologic systems which produce reinforcement for alcohol consumption and changes in brain chemistry that lead to addiction. The developmental history of neurobehavioral theories of the transition from alcohol drinking to alcohol addiction is presented and juxtaposed to the neurobiological findings. Depending on one's point of view, we may, at this point in history, know more, or less, than we think we know about the neurobiology of alcoholism.
Keywords: addiction; Alcohol Drinking; Alcohol research history; alcoholism; Brain; GABA; glutamate; Humans; Mesolimbic dopamine system; Reward

Neuroimmune signaling: a key component of alcohol abuse - Mayfield, Jody; Ferguson, Laura; Harris, R. Adron (Current Opinion in Neurobiology, 2013)
Molecular and behavioral studies corroborate a pivotal role for the innate immune system in mediating the acute and chronic effects of alcohol and support a neuroimmune hypothesis of alcohol addiction. Changes in expression of neuroimmune genes and microglial transcripts occur in postmortem brain from alcoholics and animals exposed to alcohol, and null mutant animals lacking certain innate immune genes show decreased alcohol-mediated responses. Many of the differentially expressed genes are part of the toll like receptor (TLR) signaling pathway and culminate in an increased expression of pro-inflammatory immune genes. Compounds known to inhibit inflammation, microglial activation, and neuroimmune gene expression have shown promising results in reducing alcohol-mediated behaviors in animal models, indicating that neuroimmune signaling pathways offer unexplored targets in the treatment of alcohol abuse.
Keywords: alcoholism; Alcohols; Animals; Brain; Humans; Immunity; Innate; Signal Transduction; Toll-Like Receptors

Next stop dependence-binge drinking on the road to alcoholism: Preclinical findings on its neurobiology from rat animal models - Bell, Richard L.; Franklin, Kelle M.; Hauser, Sheketha; Engleman, Eric A. (2013)

Novel subunit-specific tonic GABA currents and differential effects of ethanol in the central amygdala of CRF receptor-1 reporter mice - Herman, Melissa A.; Contet, Candice; Justice, Nicholas J.; Vale, Wylie; Roberto, Marisa (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2013)
The central nucleus of the amygdala (CeA) is an important integrative site for the reinforcing effects of drugs of abuse, such as ethanol. Activation of corticotropin-releasing factor type 1 (CRF1) receptors in the CeA plays a critical role in the development of ethanol dependence, but these neurons remain uncharacterized. Using CRF1:GFP reporter mice and a combined electrophysiological/immunohistochemical approach, we found that CRF1 neurons exhibit an α1 GABA(A) receptor subunit-mediated tonic conductance that is driven by action potential-dependent GABA release. In contrast, unlabeled CeA neurons displayed a δ subunit-mediated tonic conductance that is enhanced by ethanol. Ethanol increased the firing discharge of CRF1 neurons and decreased the firing discharge of unlabeled CeA neurons. Retrograde tracing studies indicate that CeA CRF1 neurons project into the bed nucleus of the stria terminalis. Together, these data demonstrate subunit-specific tonic signaling and provide mechanistic insight into the specific effects of ethanol on CeA microcircuitry.
Keywords: Action Potentials; Amygdala; Animals; Corticotropin-Releasing Hormone; Ethanol; GABA-A; gamma-Aminobutyric Acid; Male; Mice; Protein Subunits; Receptors; Transgenic

Opioid receptors: distinct roles in mood disorders - Lutz, Pierre-Eric; Kieffer, Brigitte L. (Trends in Neurosciences, 2013)
The roles of opioid receptors in pain and addiction have been extensively studied, but their function in mood disorders has received less attention. Accumulating evidence from animal research reveals that mu, delta and kappa opioid receptors (MORs, DORs and KORs, respectively) exert highly distinct controls over mood-related processes. DOR agonists and KOR antagonists have promising antidepressant potential, whereas the risk-benefit ratio of currently available MOR agonists as antidepressants remains difficult to evaluate, in addition to their inherent abuse liability. To date, both human and animal studies have mainly examined MORs in the etiology of depressive disorders, and future studies will address DOR and KOR function in established and emerging neurobiological aspects of depression, including neurogenesis, neurodevelopment, and social behaviors.
Keywords: Affect; Analgesics; Animals; Antidepressive Agents; Brain Chemistry; Brain-Derived Neurotrophic Factor; Comorbidity; Female; Humans; Knockout; Male; Maternal Behavior; Mice; Models; Mood Disorders; Narcotic Antagonists; Nerve Tissue Proteins; Neurogenesis; Neurological; Neuronal Plasticity; Neurotransmitter Agents; Opioid; Opioid Peptides; Pregnancy; Prenatal Exposure Delayed Effects; Receptors; Reward; Social Behavior; Substance-Related Disorders

Positively correlated miRNA-mRNA regulatory networks in mouse frontal cortex during early stages of alcohol dependence - Nunez, Yury O.; Truitt, Jay M.; Gorini, Giorgio; Ponomareva, Olga N.; Blednov, Yuri A.; Harris, R. Adron; Mayfield, R. Dayne (BMC genomics, 2013)
BACKGROUND: Although the study of gene regulation via the action of specific microRNAs (miRNAs) has experienced a boom in recent years, the analysis of genome-wide interaction networks among miRNAs and respective targeted mRNAs has lagged behind. MicroRNAs simultaneously target many transcripts and fine-tune the expression of genes through cooperative/combinatorial targeting. Therefore, they have a large regulatory potential that could widely impact development and progression of diseases, as well as contribute unpredicted collateral effects due to their natural, pathophysiological, or treatment-induced modulation. We support the viewpoint that whole mirnome-transcriptome interaction analysis is required to better understand the mechanisms and potential consequences of miRNA regulation and/or deregulation in relevant biological models. In this study, we tested the hypotheses that ethanol consumption induces changes in miRNA-mRNA interaction networks in the mouse frontal cortex and that some of the changes observed in the mouse are equivalent to changes in similar brain regions from human alcoholics. RESULTS: miRNA-mRNA interaction networks responding to ethanol insult were identified by differential expression analysis and weighted gene coexpression network analysis (WGCNA). Important pathways (coexpressed modular networks detected by WGCNA) and hub genes central to the neuronal response to ethanol are highlighted, as well as key miRNAs that regulate these processes and therefore represent potential therapeutic targets for treating alcohol addiction. Importantly, we discovered a conserved signature of changing miRNAs between ethanol-treated mice and human alcoholics, which provides a valuable tool for future biomarker/diagnostic studies in humans. We report positively correlated miRNA-mRNA expression networks that suggest an adaptive, targeted miRNA response due to binge ethanol drinking. CONCLUSIONS: This study provides new evidence for the role of miRNA regulation in brain homeostasis and sheds new light on current understanding of the development of alcohol dependence. To our knowledge this is the first report that activated expression of miRNAs correlates with activated expression of mRNAs rather than with mRNA downregulation in an in vivo model. We speculate that early activation of miRNAs designed to limit the effects of alcohol-induced genes may be an essential adaptive response during disease progression.
Keywords: alcoholism; Animals; Ethanol; Frontal Lobe; Gene Expression Profiling; Gene Regulatory Networks; Humans; Messenger; Mice; MicroRNAs; RNA; Severity of Illness Index

Predicting extinction and reinstatement of alcohol and sucrose self-administration in outbred rats - Kosten, Therese A.; Meisch, Richard A. (Experimental and Clinical Psychopharmacology, 2013)
Preventing relapse to drinking or escalation to excessive drinking could be aided by identifying factors that predict these behaviors. Animal models, particularly those that utilize operant self-administration techniques, can be useful. In a prior operant study, we noted a good deal of variability in behaviors during training and test sessions. We utilized data obtained from that study of two groups of rats, trained and tested identically except one responded for alcohol and the other for sucrose, to explore for associations related to relapse (reinstatement) or to excessive drinking (maintenance). Data were obtained from sessions conducted under fixed- and progressive-ratio schedules as well as from extinction and reinstatement sessions. Variables assessed included active and inactive presses, head entries into the dipper trough, and automated recordings of body movements during these sessions as well as alcohol preference before training. First, using multiple regression, we examined whether alcohol preference before training associated with any response variable among alcohol-responding rats. Second, using factor analysis, we identified a training variable, body movements, that associated with responses during tests. Using this measure, rats were divided into low- and high-response groups and compared on active lever presses and head entries across test sessions. Results show that among alcohol-responding rats, alcohol preference predicted head entries during extinction. High-body-movement rats emitted significantly fewer active lever presses and had fewer head entries across test sessions, particularly during reinstatement, compared with low-body-movement rats. Results from this exploratory study provide clues for future experimental studies.
Keywords: Animals; Ethanol; Movement; Rats; Self Administration; Sucrose

RNaseIII and T4 polynucleotide Kinase sequence biases and solutions during RNA-seq library construction - Lee, Changhoon; Harris, R. Adron; Wall, Jason K.; Mayfield, R. Dayne; Wilke, Claus O. (Biology Direct, 2013)
BACKGROUND: RNA-seq is a next generation sequencing method with a wide range of applications including single nucleotide polymorphism (SNP) detection, splice junction identification, and gene expression level measurement. However, the RNA-seq sequence data can be biased during library constructions resulting in incorrect data for SNP, splice junction, and gene expression studies. Here, we developed new library preparation methods to limit such biases. RESULTS: A whole transcriptome library prepared for the SOLiD system displayed numerous read duplications (pile-ups) and gaps in known exons. The pile-ups and gaps of the whole transcriptome library caused a loss of SNP and splice junction information and reduced the quality of gene expression results. Further, we found clear sequence biases for both 5' and 3' end reads in the whole transcriptome library. To remove this bias, RNaseIII fragmentation was replaced with heat fragmentation. For adaptor ligation, T4 Polynucleotide Kinase (T4PNK) was used following heat fragmentation. However, its kinase and phosphatase activities introduced additional sequence biases. To minimize them, we used OptiKinase before T4PNK. Our study further revealed the specific target sequences of RNaseIII and T4PNK. CONCLUSIONS: Our results suggest that the heat fragmentation removed the RNaseIII sequence bias and significantly reduced the pile-ups and gaps. OptiKinase minimized the T4PNK sequence biases and removed most of the remaining pile-ups and gaps, thus maximizing the quality of RNA-seq data.
Keywords: Gene Library; Hot Temperature; Polynucleotide 5'-Hydroxyl-Kinase; Ribonuclease III; RNA; Sequence Analysis; Transcriptome

Selection for drinking in the dark alters brain gene coexpression networks - Iancu, Ovidiu D.; Oberbeck, Denesa; Darakjian, Priscila; Metten, Pamela; McWeeney, Shannon; Crabbe, John C.; Hitzemann, Robert (Alcoholism, Clinical and Experimental Research, 2013)
BACKGROUND: Heterogeneous stock (HS/NPT) mice have been used to create lines selectively bred in replicate for elevated drinking in the dark (DID). Both selected lines routinely reach a blood ethanol (EtOH) concentration (BEC) of 1.00 mg/ml or greater at the end of the 4-hour period of access in Day 2. The mechanisms through which genetic differences influence DID are currently unclear. Therefore, the current study examines the transcriptome, the first stage at which genetic variability affects neurobiology. Rather than focusing solely on differential expression (DE), we also examine changes in the ways that gene transcripts collectively interact with each other, as revealed by changes in coexpression patterns. METHODS: Naïve mice (N = 48/group) were genotyped using the Mouse Universal Genotyping Array, which provided 3,683 informative markers. Quantitative trait locus (QTL) analysis used a marker-by-marker strategy with the threshold for a significant logarithm of odds (LOD) set at 10.6. Gene expression in the ventral striatum was measured using the Illumina Mouse 8.2 array. Differential gene expression and the weighted gene coexpression network analysis (WGCNA) were implemented largely as described elsewhere. RESULTS: Significant QTLs for elevated BECs after DID were detected on chromosomes 4, 14, and 16; the latter 2 were associated with gene-poor regions. None of the QTLs overlapped with known QTLs for EtOH preference drinking. Ninety-four transcripts were detected as being differentially expressed in both selected lines versus HS controls; there was no overlap with known preference genes. The WGCNA revealed 2 modules as showing significant effects of both selections on intramodular connectivity. A number of genes known to be associated with EtOH phenotypes (e.g., Gabrg1, Glra2, Grik1, Npy2r, and Nts) showed significant changes in connectivity. CONCLUSIONS: We found marked and consistent effects of selection on coexpression patterns; DE changes were more modest and less concordant. The QTLs and differentially expressed genes detected here are distinct from the preference phenotype. This is consistent with behavioral data and suggests that the DID and preference phenotypes are markedly different genetically.
Keywords: alcohol; Alcohol Drinking; Animals; Basal Ganglia; Binge; Brain Chemistry; Darkness; Drinking in the dark; Female; Gene Regulatory Networks; Genetic; Male; Mice; Microarray; Mouse; Quantitative Trait Loci; Selection; Weighted Gene Coexpression Network Analysis

Selective breeding for ethanol-related traits alters circadian phenotype - McCulley, Walter D.; Ascheid, Sonja; Crabbe, John C.; Rosenwasser, Alan M. (Alcohol (Fayetteville, N.Y.), 2013)
Previous studies in mice and rats have shown that selective breeding for high and low ethanol preference results in divergence of circadian phenotype in the selected lines. These results indicate that some alleles influencing ethanol preference also contribute to circadian rhythm regulation. Selective breeding has also been used to produce lines of mice differing in a number of other ethanol-related traits, while studies of phenotypic and genetic correlation indicate that diverse ethanol-related traits are influenced by both shared and unshared genetics. In the present study, we examined several features of circadian activity rhythms in a mouse line selected for binge-like drinking and in mouse lines selected for high and low severity of ethanol withdrawal convulsions. Specifically, Experiment 1 compared High Drinking in the Dark (HDID-1) mice to their genetically heterogeneous progenitor line (HS/Npt), and Experiment 2 compared Withdrawal Seizure-Prone (WSP-2) and Withdrawal Seizure-Resistant (WSR-2) mice. Both line pairs displayed differences in their daily activity patterns under light-dark conditions. In addition, HDID-1 mice showed shorter free-running periods in constant light and less coherent activity rhythms across lighting conditions relative to HS/Npt controls, while WSP-2 mice showed longer free-running periods in constant darkness relative to WSR-2 mice. These results strengthen the evidence for genetic linkages between responsiveness to ethanol and circadian regulation, and extend this evidence to include ethanol-related phenotypes other than preference drinking. However, the present results also indicate that the nature of genetic correlations between and within phenotypic domains is highly complex.
Keywords: Animals; Breeding; Circadian Rhythm; Ethanol; Male; Mice; Phenotype; Species Specificity

Synaptic plasticity in the hippocampus shows resistance to acute ethanol exposure in transgenic mice with astrocyte-targeted enhanced CCL2 expression - Bray, Jennifer G.; Reyes, Kenneth C.; Roberts, Amanda J.; Ransohoff, Richard M.; Gruol, Donna L. (Neuropharmacology, 2013)
It has been shown that ethanol exposure can activate astrocytes and microglia resulting in the production of neuroimmune factors, including the chemokine CCL2. The role of these neuroimmune factors in the effects of ethanol on the central nervous system has yet to be elucidated. To address this question, we investigated the effects of ethanol on synaptic transmission and plasticity in the hippocampus from mice that express elevated levels of CCL2 in the brain and their non-transgenic littermate controls. The brains of the transgenic mice simulate one aspect of the alcoholic brain, chronically increased levels of CCL2. We used extracellular field potential recordings in acutely isolated hippocampal slices to identify neuroadaptive changes produced by elevated levels of CCL2 and how these neuroadaptive changes affect the actions of acute ethanol. Results showed that synaptic transmission and the effects of ethanol on synaptic transmission were similar in the CCL2-transgenic and non-transgenic hippocampus. However, long-term potentiation (LTP), a cellular mechanism thought to underlie learning and memory, in the CCL2-transgenic hippocampus was resistant to the ethanol-induced depression of LTP observed in the non-transgenic hippocampus. Consistent with these results, ethanol pretreatment significantly impaired cued and contextual fear conditioning in non-transgenic mice, but had no effect in CCL2-transgenic mice. These data show that chronically elevated levels of CCL2 in the hippocampus produce neuroadaptive changes that block the depressing effects of ethanol on hippocampal synaptic plasticity and support the hypothesis that CCL2 may provide a neuroprotective effect against the devastating actions of ethanol on hippocampal function.
Keywords: Animals; Astrocytes; Chemokine CCL2; Ethanol; Excitatory Postsynaptic Potentials; Female; Gene Expression Regulation; Hippocampus; Humans; Inbred C57BL; Male; Mice; Neuronal Plasticity; Synapses; Transgenic

Taok2 controls behavioral response to ethanol in mice - Kapfhamer, D.; Taylor, S.; Zou, M. E.; Lim, J. P.; Kharazia, V.; Heberlein, U. (Genes, Brain, and Behavior, 2013)
Despite recent advances in the understanding of ethanol's biological action, many of the molecular targets of ethanol and mechanisms behind ethanol's effect on behavior remain poorly understood. In an effort to identify novel genes, the products of which regulate behavioral responses to ethanol, we recently identified a mutation in the dtao gene that confers resistance to the locomotor stimulating effect of ethanol in Drosophila. dtao encodes a member of the Ste20 family of serine/threonine kinases implicated in MAP kinase signaling pathways. In this study, we report that conditional ablation of the mouse dtao homolog, Taok2, constitutively and specifically in the nervous system, results in strain-specific and overlapping alterations in ethanol-dependent behaviors. These data suggest a functional conservation of dtao and Taok2 in mediating ethanol's biological action and identify Taok2 as a putative candidate gene for ethanol use disorders in humans.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Behavior; Classical; Conditioning; Ethanol; Gait Ataxia; Inbred C57BL; Locomotion; MAP Kinase Kinase Kinases; Mice; Protein-Serine-Threonine Kinases; Transgenic

Time-dependent negative reinforcement of ethanol intake by alleviation of acute withdrawal - Cunningham, Christopher L.; Fidler, Tara L.; Murphy, Kevin V.; Mulgrew, Jennifer A.; Smitasin, Phoebe J. (Biological Psychiatry, 2013)
BACKGROUND: Drinking to alleviate the symptoms of acute withdrawal is included in diagnostic criteria for alcoholism, but the contribution of acute withdrawal relief to high alcohol intake has been difficult to model in animals. METHODS: Ethanol dependence was induced by passive intragastric ethanol infusions in C57BL/6J (B6) and DBA/2J (D2) mice; nondependent control animals received water infusions. Mice were then allowed to self-administer ethanol or water intragastrically. RESULTS: The time course of acute withdrawal was similar to that produced by chronic ethanol vapor exposure in mice, reaching a peak at 7 to 9 hours and returning to baseline within 24 hours; withdrawal severity was greater in D2 than in B6 mice (experiment 1). Postwithdrawal delays in initial ethanol access (1, 3, or 5 days) reduced the enhancement in later ethanol intake normally seen in D2 (but not B6) mice allowed to self-infuse ethanol during acute withdrawal (experiment 2). The postwithdrawal enhancement of ethanol intake persisted over a 5-day abstinence period in D2 mice (experiment 3). D2 mice allowed to drink ethanol during acute withdrawal drank more ethanol and self-infused more ethanol than nondependent mice (experiment 4). CONCLUSIONS: Alcohol access during acute withdrawal increased later alcohol intake in a time-dependent manner, an effect that may be related to a genetic difference in sensitivity to acute withdrawal. This promising model of negative reinforcement encourages additional research on the mechanisms underlying acute withdrawal relief and its role in determining risk for alcoholism.
Keywords: alcoholism; Animals; Ethanol; Inbred C57BL; Inbred DBA; Male; Mice; Self Administration; Species Specificity; Substance Withdrawal Syndrome; Time Factors

Toll-like receptor 4 (Tlr4) knockout rats produced by transcriptional activator-like effector nuclease (TALEN)-mediated gene inactivation - Ferguson, Carolyn; McKay, Matthew; Harris, R. Adron; Homanics, Gregg E. (Alcohol (Fayetteville, N.Y.), 2013)
Genetically engineered mice are a valuable resource for studies of the behavioral effects of ethanol. However, for some behavioral tests of ethanol action, the rat is a superior model organism. Production of genetically engineered rats has been severely hampered due to technical limitations. Here we utilized a promising new technique for efficient site-specific gene modification to create a novel gene knockout rat line. This approach is based on transcriptional activator-like effector nucleases (TALENs). TALENs function in pairs and bind DNA in a sequence-specific manner. Upon binding to the target sequence, a functional nuclease is reconstituted that creates double-stranded breaks in the DNA that are efficiently repaired by non-homologous end joining. This error-prone process often results in deletions of varying lengths at the targeted locus. The toll-like receptor 4 (Tlr4) gene was selected for TALEN-mediated gene inactivation. Tlr4 has been implicated in ethanol-induced neuroinflammation and neurodegeneration, as well as multiple ethanol-induced behavioral effects. To generate Tlr4 knockout rats, a pair of TALEN constructs was created that specifically target Exon 1 immediately downstream of the start of translation. TALEN mRNAs were microinjected into the cytoplasm of one-cell Wistar rat embryos. Of 13 live-born pups that resulted, one harbored a mutation in Exon 1 of Tlr4. The mutated allele consisted of a 13 base-pair deletion that was predicted to create a frameshift mutation after amino acid 25. This founder rat successfully transmitted the mutation to F1 offspring. Heterozygous F1 offspring were interbred to produce homozygous F2 animals. Homozygous mutants expressed the 13-bp deletion in Tlr4 mRNA. In contrast to control rats that produced a robust increase in plasma tumor necrosis factor alpha in response to a lipopolysaccharide challenge, homozygous rats had a markedly attenuated response. Thus, the mutant Tlr4 allele generated by TALEN-mediated gene inactivation represents a null allele. This knockout rat line will be valuable for studies of ethanol action as well as more general inflammatory conditions including septic shock. In conclusion, TALEN-mediated gene targeting in rat zygotes represents an inexpensive, efficient, and rapid method for creating genetically engineered rats.
Keywords: Alleles; Animals; Deoxyribonucleases; Exons; Female; Gene Knockout Techniques; Gene Silencing; Gene targeted rats; Genome editing; Homozygote; Knockout rats; Lipopolysaccharides; Male; Messenger; Mutation; Rats; RNA; Toll-Like Receptor 4; Toll-like receptor 4 (Tlr4); Transcriptional activator-like effector nuclease (TALEN); Tumor Necrosis Factor-alpha

Whole brain and brain regional coexpression network interactions associated with predisposition to alcohol consumption - Vanderlinden, Lauren A.; Saba, Laura M.; Kechris, Katerina; Miles, Michael F.; Hoffman, Paula L.; Tabakoff, Boris (PloS One, 2013)
To identify brain transcriptional networks that may predispose an animal to consume alcohol, we used weighted gene coexpression network analysis (WGCNA). Candidate coexpression modules are those with an eigengene expression level that correlates significantly with the level of alcohol consumption across a panel of BXD recombinant inbred mouse strains, and that share a genomic region that regulates the module transcript expression levels (mQTL) with a genomic region that regulates alcohol consumption (bQTL). To address a controversy regarding utility of gene expression profiles from whole brain, vs specific brain regions, as indicators of the relationship of gene expression to phenotype, we compared candidate coexpression modules from whole brain gene expression data (gathered with Affymetrix 430 v2 arrays in the Colorado laboratories) and from gene expression data from 6 brain regions (nucleus accumbens (NA); prefrontal cortex (PFC); ventral tegmental area (VTA); striatum (ST); hippocampus (HP); cerebellum (CB)) available from GeneNetwork. The candidate modules were used to construct candidate eigengene networks across brain regions, resulting in three "meta-modules", composed of candidate modules from two or more brain regions (NA, PFC, ST, VTA) and whole brain. To mitigate the potential influence of chromosomal location of transcripts and cis-eQTLs in linkage disequilibrium, we calculated a semi-partial correlation of the transcripts in the meta-modules with alcohol consumption conditional on the transcripts' cis-eQTLs. The function of transcripts that retained the correlation with the phenotype after correction for the strong genetic influence, implicates processes of protein metabolism in the ER and Golgi as influencing susceptibility to variation in alcohol consumption. Integration of these data with human GWAS provides further information on the function of polymorphisms associated with alcohol-related traits.
Keywords: Alcohol Drinking; Animals; Brain; Female; Gene Expression Profiling; Gene Regulatory Networks; Genetic; Genetic Predisposition to Disease; Inbred Strains; Male; Mice; Models; Quantitative Trait Loci

Zinc-dependent modulation of α2- and α3-glycine receptor subunits by ethanol - McCracken, Lindsay M.; Trudell, James R.; McCracken, Mandy L.; Harris, R. Adron (Alcoholism, Clinical and Experimental Research, 2013)
BACKGROUND: Strychnine-sensitive glycine receptors (GlyRs) are expressed throughout the brain and spinal cord and are among the strongly supported protein targets of alcohol. This is based largely on studies of the α1-subunit; however, α2- and α3-GlyR subunits are as or more abundantly expressed than α1-GlyRs in multiple forebrain brain areas considered to be important for alcohol-related behaviors, and uniquely some α3-GlyRs undergo RNA editing. Nanomolar and low micromolar concentrations of zinc ions potentiate GlyR function, and in addition to zinc's effects on glycine-activated currents, we have recently shown that physiological concentrations of zinc also enhance the magnitude of ethanol (EtOH)'s effects on α1-GlyRs. METHODS: Using 2-electrode voltage-clamp electrophysiology in oocytes expressing either α2- or α3-GlyRs, we first tested the hypothesis that the effects of EtOH on α2- and α3-GlyRs would be zinc dependent, as we have previously reported for α1-GlyRs. Next, we constructed an α3P185L-mutant GlyR to test whether RNA-edited and unedited GlyRs contain differences in EtOH sensitivity. Last, we built a homology model of the α3-GlyR subunit. RESULTS: The effects of EtOH (20 to 200 mM) on both subunits were greater in the presence than in the absence of 500 nM added zinc. The α3P185L-mutation that corresponds to RNA editing increased sensitivity to glycine and decreased sensitivity to EtOH. CONCLUSIONS: Our findings provide further evidence that zinc is important for determining the magnitude of EtOH's effects at GlyRs and suggest that by better understanding zinc/EtOH interactions at GlyRs, we may better understand the sites and mechanisms of EtOH action.
Keywords: Animals; Drug Interactions; Electrophysiological Phenomena; Ethanol; Female; Gene Expression; Glycine; Glycine Receptor; Humans; Models; Molecular; Oocytes; Patch-Clamp Techniques; Rats; Receptors; Xenopus laevis; Zinc

κ-Opioid receptors in the central amygdala regulate ethanol actions at presynaptic GABAergic sites - Kang-Park, Maenghee; Kieffer, Brigitte L.; Roberts, Amanda J.; Siggins, George R.; Moore, Scott D. (The Journal of Pharmacology and Experimental Therapeutics, 2013)
Human and animal studies indicate that κ-opioid receptors (KORs) are involved in ethanol drinking and dependence (Xuei et al., 2006; Walker and Koob, 2008; Walker et al., 2011). Using in vitro single-cell recording techniques in mouse brain slices, we examined the physiologic effects of KOR activation in the central amygdala (CeA) on GABAergic neurotransmission and its interaction with acute ethanol. A selective KOR agonist (U69593, 1 μM) diminished evoked GABAergic inhibitory postsynaptic currents (IPSCs) by 18% (n = 10), whereas blockade of KORs with a selective antagonist (nor-binaltorphimine, 1 μM) augmented the baseline evoked GABAergic IPSCs by 14% (P < 0.01; n = 34), suggesting that the KOR system contributes to tonic inhibition of GABAergic neurotransmission in the CeA. In addition, the enhancement by acute ethanol of GABAergic IPSC amplitudes was further augmented by pharmacologic blockade of KORs, from 14% (n = 36) to 27% (n = 26; P < 0.01), or by genetic deletion of KORs, from 14% in wild-type mice (n = 19) to 34% in KOR knockout mice (n = 13; P < 0.01). Subsequent experiments using tetrodotoxin to block activity-dependent neurotransmission suggest that KORs regulate GABA release at presynaptic sites. Our data support the idea that KORs modulate GABAergic synaptic responses and ethanol effects as one of multiple opioid system-dependent actions of ethanol in the CeA, possibly in a circuit-specific manner.
Keywords: Amygdala; Analgesics; Animals; Anti-Anxiety Agents; Central Nervous System Depressants; Ethanol; Evoked Potentials; GABAergic Neurons; kappa; Knockout; Male; Mice; Narcotic Antagonists; Nerve Tissue Proteins; Neural Inhibition; Opioid; Patch-Clamp Techniques; Presynaptic Terminals; Receptors; Single-Cell Analysis; Sodium Channel Blockers; Synaptic Transmission

Activation and role of the medial prefrontal cortex (mPFC) in extinction of ethanol-induced associative learning in mice - Groblewski, Peter A.; Ryabinin, Andrey E.; Cunningham, Christopher L. (Neurobiology of Learning and Memory, 2012)
Although the medial prefrontal cortex (mPFC) has been shown to be integrally involved in extinction of a number of associative behaviors, its role in extinction of alcohol (ethanol)-induced associative learning has received little attention. Previous reports have provided evidence supporting a role for the mPFC in acquisition and extinction of amphetamine-induced conditioned place preference (CPP) in rats, however, it remains unknown if this region is necessary for extinction of ethanol (EtOH)-induced associative learning in mice. Using immunohistochemical analysis of phosphorylated and unphosphorylated cAMP response element-binding protein (CREB), the current set of experiments first showed that the prelimbic (PL) and infralimbic (IL) subregions of the mPFC exhibited dynamic responses in phosphorylation of CREB to a Pavlovian-conditioned, EtOH-paired cue. Interestingly, CREB phosphorylation within these regions was sensitive to manipulations of the EtOH-cue contingency-that is, the cue-induced increase of pCREB in both the PL and IL was absent following extinction. In order to confirm a functional role of the mPFC in regulating the extinction process, we then showed that electrolytic lesions of the mPFC following acquisition blocked subsequent extinction of EtOH-CPP. Together, these experiments indicate a role for the PL and IL subregions of the mPFC in processing changes of the EtOH-cue contingency, as well as in regulating extinction of EtOH-induced associative learning in mice.
Keywords: Animal; Animals; Association Learning; Behavior; Classical; Conditioning; Ethanol; Extinction; Male; Mice; Prefrontal Cortex; Psychological

Alcohol Dependence and Genes Encoding α2 and γ1 GABAA Receptor Subunits - Borghese, Cecilia M.; Harris, R. Adron (Alcohol Research : Current Reviews, 2012)
One approach to identifying the causes of alcoholism, particularly without crossing ethical boundaries in human subjects, is to look at the person’s genome (and particularly at the variations that naturally arise in the DNA) to identify those variations that seem to be found more commonly in people with the disease. Some of these analyses have focused on the genes that encode subunits of the receptor for the brain chemical (i.e., neurotransmitter) γ-aminobutyric acid (GABA). Different epidemiological genetic studies have provided evidence that variations in certain GABAA receptor (GABAA-R) subunits, particularly subunits α2 and γ1, are correlated with alcohol dependence. Manipulations of these genes and their expression in mice and rats also are offering clues as to the role of specific GABAA-Rs in the molecular mechanisms underlying alcoholism and suggest possibilities for new therapeutic approaches.

Animal models for medications development targeting alcohol abuse using selectively bred rat lines: neurobiological and pharmacological validity - Bell, Richard L.; Sable, Helen J. K.; Colombo, Giancarlo; Hyytia, Petri; Rodd, Zachary A.; Lumeng, Lawrence (Pharmacology, Biochemistry, and Behavior, 2012)
The purpose of this review paper is to present evidence that rat animal models of alcoholism provide an ideal platform for developing and screening medications that target alcohol abuse and dependence. The focus is on the 5 oldest international rat lines that have been selectively bred for a high alcohol-consumption phenotype. The behavioral and neurochemical phenotypes of these rat lines are reviewed and placed in the context of the clinical literature. The paper presents behavioral models for assessing the efficacy of pharmaceuticals for the treatment of alcohol abuse and dependence in rodents, with particular emphasis on rats. Drugs that have been tested for their effectiveness in reducing alcohol/ethanol consumption and/or self-administration by these rat lines and their putative site of action are summarized. The paper also presents some current and future directions for developing pharmacological treatments targeting alcohol abuse and dependence.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Behavior; Brain; Breeding; Disease Models; Female; Humans; Inbred Strains; Male; Neurotransmitter; Neurotransmitter Agents; Phenotype; Rats; Receptors

Behavioral actions of alcohol: phenotypic relations from multivariate analysis of mutant mouse data - Blednov, Y. A.; Mayfield, R. D.; Belknap, J.; Harris, R. A. (Genes, Brain, and Behavior, 2012)
Behavioral studies on genetically diverse mice have proven powerful for determining relationships between phenotypes and have been widely used in alcohol research. Most of these studies rely on naturally occurring genetic polymorphisms among inbred strains and selected lines. Another approach is to introduce variation by engineering single-gene mutations in mice. We have tested 37 different mutant mice and their wild-type controls for a variety (31) of behaviors and have mined this data set by K-means clustering and analysis of correlations. We found a correlation between a stress-related response (activity in a novel environment) and alcohol consumption and preference for saccharin. We confirmed several relationships detected in earlier genetic studies, including positive correlation of alcohol consumption with saccharin consumption and negative correlations with conditioned taste aversion and alcohol withdrawal severity. Introduction of single-gene mutations either eliminated or greatly diminished these correlations. The three tests of alcohol consumption used (continuous two-bottle choice and two limited access tests: drinking in the dark and sustained high alcohol consumption) share a relationship with saccharin consumption, but differ from each other in their correlation networks. We suggest that alcohol consumption is controlled by multiple physiological systems where single-gene mutations can disrupt the networks of such systems.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Choice Behavior; Ethanol; Genotype; Inbred C57BL; Mice; Phenotype; Taste; Transgenic

Behavioral characterization of knockin mice with mutations M287L and Q266I in the glycine receptor α1 subunit - Blednov, Yuri A.; Benavidez, Jill M.; Homanics, Gregg E.; Harris, R. Adron (The Journal of Pharmacology and Experimental Therapeutics, 2012)
We used behavioral pharmacology to characterize heterozygous knockin mice with mutations (Q266I or M287L) in the α1 subunit of the glycine receptor (GlyR) (J Pharmacol Exp Ther 340:304-316, 2012). These mutations were designed to reduce (M287L) or eliminate (Q266I) ethanol potentiation of GlyR function. We asked which behavioral effects of ethanol would be reduced more in the Q266I mutant than the M287L and found rotarod ataxia to be the behavior that fulfilled this criterion. Compared with controls, the mutant mice also differed in ethanol consumption, ethanol-stimulated startle response, signs of acute physical dependence, and duration of loss of righting response produced by ethanol, butanol, ketamine, pentobarbital, and flurazepam. Some of these behavioral changes were mimicked in wild-type mice by acute injections of low, subconvulsive doses of strychnine. Both mutants showed increased acoustic startle response and increased sensitivity to strychnine seizures. Thus, in addition to reducing ethanol action on the GlyRs, these mutations reduced glycinergic inhibition, which may also alter sensitivity to GABAergic drugs.
Keywords: 1-Butanol; 129 Strain; Alcohol Drinking; Alcohol Withdrawal Seizures; Amino Acid Substitution; Animal; Animals; Behavior; Central Nervous System Depressants; Classical; Conditioning; Drug Synergism; Eating; Ethanol; Female; Food Preferences; Gene Knock-In Techniques; Glycine; Inbred C57BL; Male; Mice; Motor Skills; Mutation; N-Methylaspartate; Nicotine; Pentylenetetrazole; Quinine; Receptors; Reflex; Righting; Rotarod Performance Test; Saccharin; Seizures; Sex Characteristics; Startle; strychnine; Taste Perception; Transgenic

Bridging Animal and Human Models: Translating From (and to) Animal Genetics - Barkley-Levenson, Amanda M.; Crabbe, John C. (Alcohol Research: Current Reviews, 2012)
Genetics play an important role in the development and course of alcohol abuse, and understanding genetic contributions to this disorder may lead to improved preventative and therapeutic strategies in the future. Studies both in humans and in animal models are necessary to fully understand the neurobiology of alcoholism from the molecular to the cognitive level. By dissecting the complex facets of alcoholism into discrete, well-defined phenotypes that are measurable in both human populations and animal models of the disease, researchers will be better able to translate findings across species and integrate the knowledge obtained from various disciplines. Some of the key areas of alcoholism research where consilience between human and animal studies is possible are alcohol withdrawal severity, sensitivity to rewards, impulsivity, and dysregulated alcohol consumption.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Disease Models; Ethanol; Humans; Phenotype; Substance Withdrawal Syndrome

The Central Amygdala and Alcohol: Role of γ-Aminobutyric Acid, Glutamate, and Neuropeptides - Roberto, Marisa; Gilpin, Nicholas W.; Siggins, George R. (Cold Spring Harbor Perspectives in Medicine, 2012)
Alcohol dependence is a chronically relapsing disorder characterized by compulsive drug seeking and drug taking, loss of control in limiting intake, and the emergence of a withdrawal syndrome in the absence of the drug. Accumulating evidence suggests an important role for synaptic transmission in the central amygdala (CeA) in mediating alcohol-related behaviors and neuroadaptative mechanisms associated with alcohol dependence. Acute alcohol facilitates γ-aminobutyric acid-ergic (GABAergic) transmission in CeA via both pre- and postsynaptic mechanisms, and chronic alcohol increases baseline GABAergic transmission. Acute alcohol inhibits glutamatergic transmission via effects at N-methyl-d-aspartate (NMDA) and AMPA receptors in CeA, whereas chronic alcohol up-regulates N-methyl-d-aspartate receptor (NMDAR)-mediated transmission. Pro- (e.g., corticotropin-releasing factor [CRF]) and anti-stress (e.g., NPY, nociceptin) neuropeptides affect alcohol- and anxiety-related behaviors, and also alter the alcohol-induced effects on CeA neurotransmission. Alcohol dependence produces plasticity in these neuropeptide systems, reflecting a recruitment of those systems during the transition to alcohol dependence., Alcohol has strong and persistent effects on synaptic transmission in the central amygdala. Most notably, it potentiates the GABAergic system.

Characterization of Two Mutations, M287L and Q266I, in the α1 Glycine Receptor Subunit That Modify Sensitivity to Alcohols - Borghese, Cecilia M.; Blednov, Yuri A.; Quan, Yu; Iyer, Sangeetha V.; Xiong, Wei; Mihic, S. John; Zhang, Li; Lovinger, David M.; Trudell, James R.; Homanics, Gregg E.; Harris, R. Adron (The Journal of Pharmacology and Experimental Therapeutics, 2012)
Glycine receptors (GlyRs) are inhibitory ligand-gated ion channels. Ethanol potentiates glycine activation of the GlyR, and putative binding sites for alcohol are located in the transmembrane (TM) domains between and within subunits. To alter alcohol sensitivity of GlyR, we introduced two mutations in the GlyR α1 subunit, M287L (TM3) and Q266I (TM2). After expression in Xenopus laevis oocytes, both mutants showed a reduction in glycine sensitivity and glycine-induced maximal currents. Activation by taurine, another endogenous agonist, was almost abolished in the M287L GlyR. The ethanol potentiation of glycine currents was reduced in the M287L GlyR and eliminated in Q266I. Physiological levels of zinc (100 nM) potentiate glycine responses in wild-type GlyR and also enhance the ethanol potentiation of glycine responses. Although zinc potentiation of glycine responses was unchanged in both mutants, zinc enhancement of ethanol potentiation of glycine responses was absent in M287L GlyRs. The Q266I mutation decreased conductance but increased mean open time (effects not seen in M287L). Two lines of knockin mice bearing these mutations were developed. Survival of homozygous knockin mice was impaired, probably as a consequence of impaired glycinergic transmission. Glycine showed a decreased capacity for displacing strychnine binding in heterozygous knockin mice. Electrophysiology in isolated neurons of brain stem showed decreased glycine-mediated currents and decreased ethanol potentiation in homozygous knockin mice. Molecular models of the wild-type and mutant GlyRs show a smaller water-filled cavity within the TM domains of the Q266I α1 subunit. The behavioral characterization of these knockin mice is presented in a companion article (J Pharmacol Exp Ther 340:317–329, 2012).

Cholecystokinin knock-down in the basolateral amygdala has anxiolytic and antidepressant-like effects in mice - Del Boca, C.; Lutz, P. E.; Le Merrer, J.; Koebel, P.; Kieffer, B. L. (Neuroscience, 2012)
Cholecystokinin (CCK) is a neuropeptide widely distributed in the mammalian brain. This peptide regulates many physiological functions and behaviors, such as cardio-respiratory control, thermoregulation, nociception, feeding, memory processes and motivational responses, and plays a prominent role in emotional responses including anxiety and depression. CCK-expressing brain regions involved in these functions remain unclear and their identification represents an important step towards understanding CCK function in the brain. The basolateral amygdala (BLA) is strongly involved in emotional processing and expresses high levels of CCK. In this study we examined the contribution of CCK expressed in this brain region to emotional responses in mice. To knockdown CCK specifically in the BLA, we used stereotaxic delivery of recombinant adeno-associated viral vectors expressing a CCK-targeted shRNA. This procedure efficiently reduced CCK levels locally. shCCK-treated animals showed reduced levels of anxiety in the elevated plus-maze, and lower despair-like behavior in the forced swim test. Our data demonstrate that CCK expressed in the BLA represents a key brain substrate for anxiogenic and depressant effects of the peptide. The study also suggests that elevated amygdalar CCK could contribute to panic and major depressive disorders that have been associated with CCK dysfunction in humans.
Keywords: Amygdala; Animals; Anxiety; Cholecystokinin; Computer-Assisted; Depression; Gene Knockdown Techniques; Image Processing; In Situ Hybridization; Inbred C57BL; Male; Mice; Reverse Transcriptase Polymerase Chain Reaction

Chronic self-administration of alcohol results in elevated ΔFosB: comparison of hybrid mice with distinct drinking patterns - Ozburn, Angela R.; Mayfield, R. D.; Ponomarev, Igor; Jones, Theresa A.; Blednov, Yuri A.; Harris, R. A. (BMC Neuroscience, 2012)
The inability to reduce or regulate alcohol intake is a hallmark symptom for alcohol use disorders. Research on novel behavioral and genetic models of experience-induced changes in drinking will further our knowledge on alcohol use disorders. Distinct alcohol self-administration behaviors were previously observed when comparing two F1 hybrid strains of mice: C57BL/6J x NZB/B1NJ (BxN) show reduced alcohol preference after experience with high concentrations of alcohol and periods of abstinence while C57BL/6J x FVB/NJ (BxF) show sustained alcohol preference. These phenotypes are interesting because these hybrids demonstrate the occurrence of genetic additivity (BxN) and overdominance (BxF) in ethanol intake in an experience dependent manner. Specifically, BxF exhibit sustained alcohol preference and BxN exhibit reduced alcohol preference after experience with high ethanol concentrations; however, experience with low ethanol concentrations produce sustained alcohol preference for both hybrids. In the present study, we tested the hypothesis that these phenotypes are represented by differential production of the inducible transcription factor, ΔFosB, in reward, aversion, and stress related brain regions.
Keywords: Alcohol preference or consumption; Hybrid mice; Two-bottle choice; ΔFosB or FosB

Corticotropin releasing factor acting on corticotropin releasing factor receptor type 1 is critical for binge alcohol drinking in mice - Kaur, Simranjit; Li, Ju; Stenzel-Poore, Mary P.; Ryabinin, Andrey E. (Alcoholism, Clinical and Experimental Research, 2012)
Background The corticotropin releasing factor (CRF) system has been implicated in the regulation of alcohol consumption. However, previous mouse knockout (KO) studies using continuous ethanol access have failed to conclusively confirm this. Recent studies have shown that CRF receptor 1 (CRFR1) antagonists attenuate alcohol intake in the limited access “drinking in the dark” (DID) model of binge drinking. To avoid the potential non-specific effects of antagonists, in the present study we tested alcohol drinking in CRFR1, CRFR2, CRF and Ucn1 KO and corresponding wild-type (WT) littermates using the DID paradigm. Methods On days 1–3, the CRFR1, CRFR2, Ucn1 and CRF KO mice and their respective wildtype (WT) littermates were provided with 20% ethanol or 10% sucrose for 2 hours with water available at all other times. On day 4, access to ethanol or sucrose was increased to 4 hours. At the end of each drinking session, the volume of ethanol consumed was recorded and at the conclusion of the last session, blood was also collected for blood ethanol concentration (BEC) analysis. Results CRFR1 KO mice had lower alcohol intakes and BECs and higher intakes of sucrose compared to WTs. In contrast, CRFR2 KO mice, while having reduced intakes initially, had similar alcohol intakes on days 2–4 and similar BECs as the WTs. In order to determine the ligand responsible, Ucn1 and CRF KO and WT mice were tested next. While Ucn1 KOs had similar alcohol intakes and BECs to their WTs, CRF KO mice showed reduced alcohol consumption and lower BECs compared to WTs. Conclusions Our results confirm that CRFR1 plays a key role in binge drinking and identify CRF as the ligand critically involved in excessive alcohol consumption.

Corticotropin-releasing factor: innocent until proven guilty - Giardino, William J.; Ryabinin, Andrey E. (Nature Reviews Neuroscience, 2012)

Cues predicting drug or food reward restore morphine-induced place conditioning in mice lacking delta opioid receptors - Le Merrer, Julie; Faget, Lauren; Matifas, Audrey; Kieffer, Brigitte L. (Psychopharmacology, 2012)
RATIONALE: The exact role of delta opioid receptors in drug-induced conditioned place preference (CPP) remains debated. Under classical experimental conditions, morphine-induced CPP is decreased in mice lacking delta opioid receptors (Oprd1 (-/-)). Morphine self-administration, however, is maintained, suggesting that drug-context association rather than drug reward is deficient in these animals. OBJECTIVES: This study further examined the role of delta opioid receptors in mediating drug-cue associations, which are necessary for the expression of morphine-induced CPP. METHODS: We first identified experimental conditions under which Oprd1 (-/-) mice are able to express CPP to morphine (5, 10 or 20 mg/kg) in a drug-free state and observed that, in this paradigm, CPP was dependent on circadian time conditions. We then took advantage of this particularity to assess the ability of various cues (internal or discrete), predicting either drug or food reward, to restore CPP induced by morphine (10 mg/kg) in Oprd1 (-/-) mice in conditions under which they normally fail to express CPP. RESULTS: We found that presentation of circadian, drug or auditory cues, predicting morphine or food reward, restored morphine CPP in Oprd1 (-/-) mice, which then performed as well as control mice. CONCLUSIONS: This study reveals that, in contrast to spatial cues, internal or discrete morphine-predicting stimuli permit full expression of morphine CPP in Oprd1 (-/-) mice. Delta receptors, therefore, appear to play a crucial role in modulating spatial contextual cue-related responses. This activity may be critical when context gains control over behavior, as is the case for context-induced relapse in drug abuse.
Keywords: Analgesics; Animal; Animals; Behavior; Circadian Rhythm; Classical; Conditioning; Cues; delta; Dose-Response Relationship; Drug; FEEDING BEHAVIOR; Female; Knockout; Male; Mice; Morphine; Opioid; Receptors; Reward

Daily patterns of ethanol drinking in adolescent and adult, male and female, high alcohol drinking (HAD) replicate lines of rats - Dhaher, Ronnie; McConnell, Kathleen K.; Rodd, Zachary A.; McBride, William J.; Bell, Richard L. (Pharmacology, biochemistry, and behavior, 2012)
The rationale for our study was to determine the pattern of ethanol drinking by the high alcohol-drinking (HAD) replicate lines of rats during adolescence and adulthood in both male and female rats. Rats were given 30 days of 24 h free-choice access to ethanol (15%, v/v) and water, with ad lib access to food, starting at the beginning of adolescence (PND 30) or adulthood (PND 90). Water and alcohol drinking patterns were monitored 22 h/day with a “lickometer” set-up. The results indicated that adolescent HAD-1 and HAD-2 males consumed the greatest levels of ethanol and had the most well defined ethanol licking binges among the age and sex groups with increasing levels of ethanol consumption throughout adolescence. In addition, following the first week of adolescence, male and female HAD-1 and HAD-2 rats differed in both ethanol consumption levels and ethanol licking behavior. Adult HAD-1 male and female rats did not differ from one another and their ethanol intake or licking behaviors did not change significantly over weeks. Adult HAD-2 male rats maintained a relatively constant level of ethanol consumption across weeks, whereas adult HAD-2 female rats increased ethanol consumption levels over weeks, peaking during the third week when they consumed more than their adult male counterparts. The results indicate that the HAD rat lines could be used as an effective animal model to examine the development of ethanol consumption and binge drinking in adolescent male and female rats providing information on the long-range consequences of adolescent alcohol drinking.

Dependence induced increases in intragastric alcohol consumption in mice - Fidler, Tara L.; Powers, Matthew S.; Ramirez, Jason J.; Crane, Andrew; Mulgrew, Jennifer; Smitasin, Phoebe; Cunningham, Christopher L. (Addiction Biology, 2012)
Three experiments used the intragastric alcohol consumption (IGAC) procedure to examine the effects of variations in passive ethanol exposure on withdrawal and voluntary ethanol intake in two inbred mouse strains, C57BL/6J (B6) and DBA/2J (D2). Experimental treatments were selected to induce quantitative differences in ethanol dependence and withdrawal severity by: (1) varying the periodicity of passive ethanol exposure (three, six or nine infusions/day); (2) varying the dose per infusion (low, medium or high); and (3) varying the duration of passive exposure (3, 5 or 10 days). All experiments included control groups passively exposed to water. B6 mice generally self-infused more ethanol than D2 mice, but passive ethanol exposure increased IGAC in both strains, with D2 mice showing larger relative increases during the first few days of ethanol access. Bout data supported the characterization of B6 mice as sippers and D2 mice as gulpers. Three larger infusions per day produced a stronger effect on IGAC than six or nine smaller infusions, especially in D2 mice. Increased IGAC was strongly predicted by cumulative ethanol dose and intoxication during passive exposure in both strains. Withdrawal during the passive exposure phase was also a strong predictor of increased IGAC in D2 mice. However, B6 mice showed little withdrawal, precluding analysis of its potential role. Overall, these data support the hypothesis that dependence-induced increases in IGAC are jointly determined by two processes that might vary across genotypes: (1) tolerance to aversive postabsorptive ethanol effects and (2) negative reinforcement (i.e. alleviation of withdrawal by self-administered ethanol).
Keywords: alcoholism; Animal; Animals; Central Nervous System Depressants; Dose-Response Relationship; Drug; Drug Administration Routes; Drug Tolerance; Ethanol; Gastrointestinal; Inbred C57BL; Inbred DBA; Intubation; Male; Mice; Models; Reinforcement (Psychology); Self Administration; Severity of Illness Index; Substance Withdrawal Syndrome; Time Factors; Water

Detection of Expression Quantitative Trait Loci in Complex Mouse Crosses: Impact and Alleviation of Data Quality and Complex Population Substructure - Iancu, Ovidiu D.; Darakjian, Priscila; Kawane, Sunita; Bottomly, Daniel; Hitzemann, Robert; McWeeney, Shannon (Frontiers in Genetics, 2012)
Complex Mus musculus crosses, e.g., heterogeneous stock (HS), provide increased resolution for quantitative trait loci detection. However, increased genetic complexity challenges detection methods, with discordant results due to low data quality or complex genetic architecture. We quantified the impact of theses factors across three mouse crosses and two different detection methods, identifying procedures that greatly improve detection quality. Importantly, HS populations have complex genetic architectures not fully captured by the whole genome kinship matrix, calling for incorporating chromosome specific relatedness information. We analyze three increasingly complex crosses, using gene expression levels as quantitative traits. The three crosses were an F2 intercross, a HS formed by crossing four inbred strains (HS4), and a HS (HS-CC) derived from the eight lines found in the collaborative cross. Brain (striatum) gene expression and genotype data were obtained using the Illumina platform. We found large disparities between methods, with concordance varying as genetic complexity increased; this problem was more acute for probes with distant regulatory elements (trans). A suite of data filtering steps resulted in substantial increases in reproducibility. Genetic relatedness between samples generated overabundance of detected eQTLs; an adjustment procedure that includes the kinship matrix attenuates this problem. However, we find that relatedness between individuals is not evenly distributed across the genome; information from distinct chromosomes results in relatedness structure different from the whole genome kinship matrix. Shared polymorphisms from distinct chromosomes collectively affect expression levels, confounding eQTL detection. We suggest that considering chromosome specific relatedness can result in improved eQTL detection.

Development of an oral operant nicotine/ethanol co-use model in alcohol-preferring (p) rats - Hauser, Sheketha R.; Katner, Simon N.; Deehan, Gerald A.; Ding, Zheng-Ming; Toalston, Jamie E.; Scott, Briana J.; Bell, Richard L.; McBride, William J.; Rodd, Zachary A. (Alcoholism, Clinical and Experimental Research, 2012)
BACKGROUND: Alcohol abuse is frequently associated with nicotine (Nic) use. The current experiments were conducted to establish an oral operant ethanol + Nic (EtOH + Nic) co-use model and to characterize some aspects of EtOH + Nic co-use. METHODS: Rats were allowed to choose between EtOH alone or EtOH + Nic solutions. Additionally, alcohol-preferring (P) rats were allowed to concurrently self-administer 3 distinct EtOH solutions (10, 20, and 30%) with varying amounts of Nic (0.07, 0.14, or 0.21 mg/ml) under operant conditions. P rats were also allowed to concurrently self-administer 2 distinct amounts of Nic (0.07 and 0.14 mg/ml) added to saccharin (Sacc; 0.025%) solutions. RESULTS: During acquisition, P rats responded for the EtOH + Nic solutions at the same level as for EtOH alone, and responding for EtOH + Nic solutions was present throughout all drinking conditions. P rats also readily maintained stable self-administration behaviors for Nic + Sacc solutions. The results demonstrated that P rats readily acquired and maintained stable self-administration behaviors for EtOH + 0.07 and EtOH + 0.14 mg/ml Nic solutions. Self-administration of EtOH + 0.21 mg/ml Nic was established in only 50% of the subjects. P rats readily expressed seeking behaviors for the EtOH + Nic solutions and reacquired EtOH + Nic self-administration during relapse testing. In addition, tail blood samples indicated that EtOH + Nic co-use resulted in pharmacologically relevant levels of both EtOH and Nic in the blood. CONCLUSIONS: Overall, the results indicate that P rats readily consume EtOH + Nic solutions concurrently in the presence of EtOH alone, express drug-seeking behaviors, and will concurrently consume physiologically relevant levels of both drugs. These results support the idea that this oral operant EtOH + Nic co-use model would be suitable for studying the development of co-abuse and the consequences of long-term chronic co-abuse.
Keywords: Addictive; Administration; Alcohol Drinking; Animal; Animals; Behavior; Conditioning; Ethanol; Female; Models; Nicotine; Operant; Oral; Rats; Reinforcement Schedule; Self Administration; Tobacco Use Disorder

Discrimination of ethanol-nicotine drug mixtures in mice: dual interactive mechanisms of overshadowing and potentiation - Ford, Matthew M.; McCracken, Aubrey D.; Davis, Natalie L.; Ryabinin, Andrey E.; Grant, Kathleen A. (Psychopharmacology, 2012)
RATIONALE: One possible basis for the proclivity of ethanol and nicotine co-abuse is an interaction between the discriminative stimulus (S(D)) effects of each drug. OBJECTIVES: The current work sought to assess the discriminative control of ethanol and nicotine cues in mice trained with drug mixtures and to determine whether interactive mechanisms of overshadowing and potentiation occur. METHODS: Male C57BL/6J mice were trained to discriminate ethanol (1.5 g/kg) alone or ethanol plus nicotine (0.4, 0.8, or 1.2 mg/kg base) in experiment 1 and nicotine (0.8 mg/kg) alone or nicotine plus ethanol (0.5, 1.0, or 2.0 g/kg) in experiment 2. Stimulus generalizations of the training mixtures to ethanol, nicotine, and the drug combination were assessed. RESULTS: Ethanol (1.5 g/kg) retained discriminative control despite the inclusion of a progressively larger nicotine dose within the training mixtures in experiment 1. Although the nicotine S(D) was overshadowed by ethanol training doses > 0.5 g/kg in experiment 2, nicotine did potentiate the effects of low-dose ethanol. CONCLUSIONS: These findings are suggestive of dual mechanisms whereby ethanol (>0.5 g/kg) overshadows the S(D) effects of nicotine, and at lower doses (<1 g/kg) the salience of ethanol's S(D) effects is potentiated by nicotine. These mechanisms may contribute to the escalation of concurrent drinking and smoking in a binge-like fashion.
Keywords: Animals; Cues; Discrimination Learning; Dose-Response Relationship; Drug; Drug Interactions; Ethanol; Inbred C57BL; Male; Mice; Nicotine; Nicotinic Agonists

Ethanol drinking microstructure of a high drinking in the dark selected mouse line - Barkley-Levenson, Amanda M.; Crabbe, John C. (Alcoholism, Clinical and Experimental Research, 2012)
BACKGROUND: The High Drinking in the Dark (HDID) selected mouse line was bred for high blood ethanol (EtOH) concentration (BEC) following the limited access drinking in the dark (DID) test and is a genetic animal model of binge-like drinking. This study examines the microstructure of EtOH drinking in these mice and their control line during 3 versions of the DID test to determine how drinking structure differences might relate to overall intake and BEC. METHODS: Male mice from the HDID-1 replicate line and HS/Npt progenitor stock were tested in separate experiments on 2- and 4-day versions of the DID test, and on a 2-day 2-bottle choice DID test with 20% EtOH and water. Testing took place in home cages connected to a continuous fluid intake monitoring system, and drinking during the DID test was analyzed for drinking microstructure. RESULTS: HDID-1 mice had more drinking bouts, shorter interbout interval, larger bout size, greater total EtOH intake, and higher BECs than HS/Npt mice on the second day of the 2-day DID test. The 4-day DID test showed greater bout size, total EtOH intake, and BEC in the HDID-1 mice than the HS/Npt mice. Total EtOH intake and BECs for the HDID-1 mice in the DID tests averaged 2.6 to 3.0 g/kg and 0.4 to 0.5 mg/ml, respectively. The 2-bottle choice test showed no genotype differences in drinking microstructure or total consumption but did show greater preference for the EtOH solution in HDID-1 mice than HS/Npt. CONCLUSIONS: These results suggest that inherent differences in EtOH drinking structure between the HDID-1 and HS/Npt mice, especially the larger bout size in the HDID-1 mice, contribute to the difference in intake during the standard DID test.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Central Nervous System Depressants; Choice Behavior; Darkness; Ethanol; Genotype; Male; Mice

Ethanol Sensitivity in High Drinking in the Dark Selectively Bred Mice - Crabbe, John C.; Kruse, Lauren C.; Colville, Alexandre M.; Cameron, Andy J.; Spence, Stephanie E.; Schlumbohm, Jason P.; Huang, Lawrence C.; Metten, Pamela (Alcoholism: Clinical and Experimental Research, 2012)
Background Mouse lines are being selectively bred in replicate for high blood ethanol concentrations (BECs) achieved after a short period of ethanol (EtOH) drinking early in the circadian dark phase. High Drinking in the Dark-1 (HDID-1) mice were in selected generation S18, and the replicate HDID-2 line in generation S11. Methods To determine other traits genetically correlated with high DID, we compared naïve animals from both lines with the unselected, segregating progenitor stock, HS/Npt. Differences between HDID-1 and HS would imply commonality of genetic influences on DID and these traits. Results HDID-1 mice showed less basal activity, greater EtOH stimulated activity, and greater sensitivity to EtOH-induced foot slips than HS. They showed lesser sensitivity to acute EtOH hypothermia and longer duration loss of righting reflex than HS. HDID-1 and control HS lines did not differ in sensitivity on 2 measures of intoxication, the balance beam and the accelerating rotarod. None of the acute response results could be explained by differences in EtOH metabolism. HDID-2 differed from HS on some, but not all, of the above responses. Conclusions These results show that some EtOH responses share common genetic control with reaching high BECs after DID, a finding consistent with other data regarding genetic contributions to EtOH responses.
Keywords: Activity; Ataxia; Genetic Correlation; High Drinking in the Dark Mice; Hypothermia; Loss of Righting Reflex; Selected Mouse Lines

Ethanol tolerance and withdrawal severity in high drinking in the dark selectively bred mice - Crabbe, John C.; Colville, Alexandre M.; Kruse, Lauren C.; Cameron, Andy J.; Spence, Stephanie E.; Schlumbohm, Jason P.; Huang, Lawrence C.; Metten, Pamela (Alcoholism, Clinical and Experimental Research, 2012)
BACKGROUND: Mouse lines are being selectively bred in replicate for high blood ethanol concentrations (BECs) achieved after limited access of ethanol (EtOH) drinking early in the circadian dark phase. High Drinking in the Dark-1 (HDID-1) mice are in selected generation S21, and the replicate HDID-2 line in generation S14. Tolerance and withdrawal symptoms are 2 of the 7 diagnostic criteria for alcohol dependence. Withdrawal severity has been found in mouse studies to be negatively genetically correlated with EtOH preference drinking. METHODS: To determine other traits genetically correlated with high DID, we compared naïve animals from both lines with the unselected, segregating progenitor stock, HS/Npt. Differences between HDID-1 and HS would imply commonality of genetic influences on DID and these traits. RESULTS: Female HDID-1 and HDID-2 mice tended to develop less tolerance than HS to EtOH hypothermia after their third daily injection. A trend toward greater tolerance was seen in the HDID males. HDID-1, HDID-2, and control HS lines did not differ in the severity of acute or chronic withdrawal from EtOH as indexed by the handling-induced convulsion (HIC). Both HDID-1 and HDID-2 mice tended to have greater HIC scores than HS regardless of drug treatment. CONCLUSIONS: These results show that tolerance to EtOH's hypothermic effects may share some common genetic control with reaching high BECs after DID, a finding consistent with other data regarding genetic contributions to EtOH responses. Withdrawal severity was not negatively genetically correlated with DID, unlike its correlation with preference drinking, underscoring the genetic differences between preference drinking and DID. HDID lines showed greater basal HIC scores than HS, suggestive of greater central nervous system excitability.
Keywords: Alcohol Drinking; Animals; Breeding; Circadian Rhythm; Drug Tolerance; Ethanol; Female; Male; Mice; Mutant Strains; Severity of Illness Index; Species Specificity; Substance Withdrawal Syndrome; Transgenic

Ethanol up-regulates nucleus accumbens neuronal activity dependent pentraxin (Narp): implications for alcohol-induced behavioral plasticity - Ary, Alexis W.; Cozzoli, Debra K.; Finn, Deborah A.; Crabbe, John C.; Dehoff, Marlin H.; Worley, Paul F.; Szumlinski, Karen K. (Alcohol (Fayetteville, N.Y.), 2012)
Neuronal activity dependent pentraxin (Narp) interacts with α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate (AMPA) glutamate receptors to facilitate excitatory synapse formation by aggregating them at established synapses. Alcohol is well-characterized to influence central glutamatergic transmission, including AMPA receptor function. Herein, we examined the influence of injected and ingested alcohol upon Narp protein expression, as well as basal Narp expression in mouse lines selectively bred for high blood alcohol concentrations under limited access conditions. Alcohol up-regulated accumbens Narp levels, concomitant with increases in levels of the GluR1 AMPA receptor subunit. However, accumbens Narp or GluR1 levels did not vary as a function of selectively bred genotype. We next employed a Narp knock-out (KO) strategy to begin to understand the behavioral relevance of alcohol-induced changes in protein expression in several assays of alcohol reward. Compared to wild-type mice, Narp KO animals: fail to escalate daily intake of high alcohol concentrations under free-access conditions; shift their preference away from high alcohol concentrations with repeated alcohol experience; exhibit a conditioned place-aversion in response to the repeated pairing of 3 g/kg alcohol with a distinct environment and fail to exhibit alcohol-induced locomotor hyperactivity following repeated alcohol treatment. Narp deletion did not influence the daily intake of either food or water, nor did it alter any aspect of spontaneous or alcohol-induced motor activity, including the development of tolerance to its motor-impairing effects with repeated treatment. Taken together, these data indicate that Narp induction, and presumably subsequent aggregation of AMPA receptors, may be important for neuroplasticity within limbic subcircuits mediating or maintaining the rewarding properties of alcohol.
Keywords: alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; AMPA; Animal; Animals; Behavior; C-Reactive Protein; Conditioning; Ethanol; Inbred C57BL; Male; Mice; Nerve Tissue Proteins; Neuronal Plasticity; Neurons; Nucleus Accumbens; Operant; Receptors; Reward; Up-Regulation

Ethanol Withdrawal-Associated Drinking and Drinking in the Dark: Common and Discrete Genetic Contributions - Crabbe, John C.; Metten, Pamela; Huang, Lawrence C.; Schlumbohm, Jason P.; Spence, Stephanie E.; Barkley-Levenson, Amanda M.; Finn, Deborah A.; Rhodes, Justin S.; Cameron, Andy J. (Addiction genetics, 2012)
Individual mice differ in the dose of ethanol they will ingest voluntarily when it is offered during limited access periods in the circadian dark, a phenotype called drinking in the dark (DID). Substantial genetic variation in DID has been reported across a few standard inbred mouse strains, and a line of High Drinking in the Dark (HDID) mice has been established through selective breeding on the blood ethanol concentration (BEC) they attain at the end of a drinking session. Here, we report ethanol DID data for 23 inbred mouse strains, including 11 not previously reported, corroborating the genetic contributions to this trait. We also report data on a different ethanol drinking trait, the increased intake seen after multiple cycles of chronic intermittent exposure to ethanol vapor (CIE). Drinking escalated significantly during ethanol withdrawal. However, HDID mice and their HS controls showed equivalent escalation during withdrawal, demonstrating that withdrawal-associated drinking escalation is not a clear genetic correlate of selection on DID. Across inbred strains, DID is substantially genetically correlated with previously-published two-bottle ethanol preference drinking data assessed under conditions of continuous ethanol access. Although inbred strain data for withdrawal-associated drinking are not available, the current pattern of results suggests that withdrawal-associated drinking is genetically distinct from DID, while genetic contributions to DID and two-bottle preference drinking are substantially similar.

Ethanol withdrawal-induced motor impairment in mice - Philibin, Scott D.; Cameron, Andy J.; Schlumbohm, Jason P.; Metten, Pamela; Crabbe, John C. (Psychopharmacology, 2012)
RATIONALE: Human ethanol withdrawal manifests as multiple behavioral deficits with distinct time courses. Most studies with mice index ethanol withdrawal severity with the handling-induced convulsion (HIC). Using the accelerating rotarod (ARR), we recently showed that ethanol withdrawal produced motor impairment. OBJECTIVES: This study aimed (a) to characterize further the ARR withdrawal trait, (b) to assess generalizability across additional behavioral assays, and (c) to test the genetic correlation between ethanol withdrawal ARR impairment and HICs. RESULTS: The severity of the ARR performance deficit depends on ethanol vapor dose and exposure duration, and lasts 1-4 days. Fatigue could not explain the deficits, which were also evident after intermittent exposure to ethanol vapor. Withdrawing mice were also impaired on a balance beam, but not on a static dowel or in foot slip errors per distance traveled in the parallel rod floor test, where they showed reduced locomotor activity. To assess genetic influences, we compared Withdrawal Seizure-Prone and -Resistant mice, genetically selected to express severe vs. mild withdrawal HICs, respectively. The ARR scores were approximately equivalent in all groups treated with ethanol vapor, though Withdrawal Seizure-Prone (WSP) mice may have displayed a slightly more severe deficit as control-treated WSP mice performed better than control-treated Withdrawal Seizure-Resistant mice. CONCLUSIONS: These studies show that ethanol withdrawal motor impairment is sensitive to a range of ethanol doses and lasts for several days. Multiple assays of behavioral impairment are affected, but the effects depend on the assay employed. Genetic contributions to withdrawal-induced ARR impairment appear largely distinct from those leading to severe or mild HICs.
Keywords: Administration; Animals; Dose-Response Relationship; Drug; Ethanol; Fatigue; Inhalation; Male; Mice; Motor Skills; Neurologic Mutants; Outbred Strains; Rotarod Performance Test; Seizures; Species Specificity; Substance Withdrawal Syndrome; Time Factors

Gene coexpression networks in human brain identify epigenetic modifications in alcohol dependence - Ponomarev, Igor; Wang, Shi; Zhang, Lingling; Harris, R. Adron; Mayfield, R. Dayne (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2012)
Alcohol abuse causes widespread changes in gene expression in human brain, some of which contribute to alcohol dependence. Previous microarray studies identified individual genes as candidates for alcohol phenotypes, but efforts to generate an integrated view of molecular and cellular changes underlying alcohol addiction are lacking. Here, we applied a novel systems approach to transcriptome profiling in postmortem human brains and generated a systemic view of brain alterations associated with alcohol abuse. We identified critical cellular components and previously unrecognized epigenetic determinants of gene coexpression relationships and discovered novel markers of chromatin modifications in alcoholic brain. Higher expression levels of endogenous retroviruses and genes with high GC content in alcoholics were associated with DNA hypomethylation and increased histone H3K4 trimethylation, suggesting a critical role of epigenetic mechanisms in alcohol addiction. Analysis of cell-type-specific transcriptomes revealed remarkable consistency between molecular profiles and cellular abnormalities in alcoholic brain. Based on evidence from this study and others, we generated a systems hypothesis for the central role of chromatin modifications in alcohol dependence that integrates epigenetic regulation of gene expression with pathophysiological and neuroadaptive changes in alcoholic brain. Our results offer implications for epigenetic therapeutics in alcohol and drug addiction.
Keywords: alcoholism; Brain; Epigenesis; Female; Gene Expression Regulation; Gene Regulatory Networks; Genetic; Humans; Male

Gene expression in the ventral tegmental area of 5 pairs of rat lines selectively bred for high or low ethanol consumption - McBride, William J.; Kimpel, Mark W.; McClintick, Jeanette N.; Ding, Zheng-Ming; Hyytia, Petri; Colombo, Giancarlo; Edenberg, Howard J.; Lumeng, Lawrence; Bell, Richard L. (Pharmacology, Biochemistry, and Behavior, 2012)
The objective of this study was to determine if there are common innate differences in gene expression or gene pathways in the ventral tegmental area (VTA) among 5 different pairs of rat lines selectively bred for high (HEC) or low (LEC) ethanol consumption: (a) alcohol-preferring (P) vs. alcohol-non-preferring (NP) rats; (b) high-alcohol-drinking (HAD) vs. low-alcohol-drinking (LAD) rats (replicate line pairs 1 and 2); (c) ALKO alcohol (AA) vs. nonalcohol (ANA) rats; and (d) Sardinian alcohol-preferring (sP) vs. alcohol-nonpreferring (sNP) rats. Microarray analysis revealed between 370 and 1340 unique named genes that significantly differed in expression between the individual line-pairs. Analysis using Gene Ontology (GO) and Ingenuity Pathways information indicated significant categories and networks in common for up to 3 line-pairs, but not for all 5 line-pairs; moreover, there were few genes in common in these categories and networks. ANOVA of the combined data for the 5 line-pairs indicated 1295 significant (p<0.01) differences in expression of named genes. Although no individual named gene was significant across all 5 line-pairs, there were 22 genes that overlapped in the same direction in 3 or 4 of the line-pairs. Overall, the findings suggest that (a) some biological categories or networks may be in common for subsets of line-pairs; and (b) regulation of different genes and/or combinations of multiple biological systems (e.g., transcription, synaptic function, intracellular signaling and protection against oxidative stress) within the VTA (possibly involving dopamine and glutamate) may be contributing to the disparate alcohol drinking behaviors of these line-pairs.
Keywords: Animals; Dose-Response Relationship; Drug; Ethanol; Gene Expression Profiling; Oligonucleotide Array Sequence Analysis; Rats

Gene Expression Under the Influence: Transcriptional Profiling of Ethanol in the Brain - Contet, Candice (Current Psychopharmacology, 2012)
Sensitivity to ethanol intoxication, propensity to drink ethanol and vulnerability to develop alcoholism are all influenced by genetic factors. Conversely, exposure to ethanol or subsequent withdrawal produce gene expression changes, which, in combination with environmental variables, may participate in the emergence of compulsive drinking and relapse. The present review offers an integrated perspective on brain gene expression profiling in rodent models of predisposition to differential ethanol sensitivity or consumption, in rats and mice subjected to acute or chronic ethanol exposure, as well as in human alcoholics. The functional categories over-represented among differentially expressed genes suggest that the transcriptional effects of chronic ethanol consumption contribute to the neuroplasticity and neurotoxicity characteristic of alcoholism. Importantly, ethanol produces distinct transcriptional changes within the different brain regions involved in intoxication, reinforcement and addiction. Special emphasis is put on recent profiling studies that have provided some insights into the molecular mechanisms potentially mediating genome-wide regulation of gene expression by ethanol. In particular, current evidence for a role of transcription factors, chromatin remodeling and microRNAs in coordinating the expression of large sets of genes in animals predisposed to excessive ethanol drinking or exposed to protracted abstinence, as well as in human alcoholics, is presented. Finally, studies that have compared ethanol with other drugs of abuse have highlighted common gene expression patterns that may play a central role in drug addiction. The availability of novel technologies and a focus on mechanistic approaches are shaping the future of ethanol transcriptomics.
Keywords: alcohol; Brain; Ethanol; Gene Expression; Microarray; profiling; RNA-seq; Transcriptome

Genes contributing to the development of alcoholism: an overview - Edenberg, Howard J. (Alcohol research : current reviews, 2012)

Genes encoding enzymes involved in ethanol metabolism - Hurley, Thomas D.; Edenberg, Howard J. (Alcohol Research: Current Reviews, 2012)
The effects of beverage alcohol (ethanol) on the body are determined largely by the rate at which it and its main breakdown product, acetaldehyde, are metabolized after consumption. The main metabolic pathway for ethanol involves the enzymes alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH). Seven different ADHs and three different ALDHs that metabolize ethanol have been identified. The genes encoding these enzymes exist in different variants (i.e., alleles), many of which differ by a single DNA building block (i.e., single nucleotide polymorphisms [SNPs]). Some of these SNPs result in enzymes with altered kinetic properties. For example, certain ADH1B and ADH1C variants that are commonly found in East Asian populations lead to more rapid ethanol breakdown and acetaldehyde accumulation in the body. Because acetaldehyde has harmful effects on the body, people carrying these alleles are less likely to drink and have a lower risk of alcohol dependence. Likewise, an ALDH2 variant with reduced activity results in acetaldehyde buildup and also has a protective effect against alcoholism. In addition to affecting drinking behaviors and risk for alcoholism, ADH and ALDH alleles impact the risk for esophageal cancer.
Keywords: Acetaldehyde; Alcohol Dehydrogenase; alcoholism; Aldehyde Dehydrogenase; Ethanol; Humans

The INIA19 Template and NeuroMaps Atlas for Primate Brain Image Parcellation and Spatial Normalization - Rohlfing, Torsten; Kroenke, Christopher D.; Sullivan, Edith V.; Dubach, Mark F.; Bowden, Douglas M.; Grant, Kathleen; Pfefferbaum, Adolf (Frontiers in Neuroinformatics, 2012)
The INIA19 is a new, high-quality template for imaging-based studies of non-human primate brains created from high-resolution T1-weighted magnetic resonance (MR) images of 19 rhesus macaque (Macaca mulatta) animals. Combined with the comprehensive cortical and subcortical label map of the NeuroMaps atlas, the INIA19 is equally suitable for studies requiring both spatial normalization and atlas label propagation. Population-averaged template images are provided for both the brain and the whole head, to allow alignment of the atlas with both skull-stripped and unstripped data, and thus to facilitate its use for skull stripping of new images. This article describes the construction of the template using freely-available software tools, as well as the template itself, which is being made available to the scientific community (http://nitrc.org/projects/inia19/).
Keywords: Brain Atlas; Macaca mulatta; Magnetic Resonance Imaging; minimum-deformation template; NeuroMaps; rhesus macaque

Intermittent availability of ethanol does not always lead to elevated drinking in mice - Crabbe, John C.; Harkness, John H.; Spence, Stephanie E.; Huang, Lawrence C.; Metten, Pamela (Alcohol and Alcoholism (Oxford, Oxfordshire), 2012)
AIMS: Intermittent access (IA) to an alcohol (ethanol) solution can lead rats to higher ethanol intakes than continuous access, and a recent report showed increased drinking in C57BL/6J mice offered 20% ethanol vs. water 3X/week (Prior studies have offered ethanol during 24 h periods, either continuously or intermittently.). METHODS: We tested the high-preference C57BL/6J inbred mice: we also studied High Drinking in the Dark (HDID) mice, a line we have selectively bred to reach intoxicating blood ethanol levels after a short period of access to a single bottle of 20% ethanol. RESULTS: Neither HDID or C57BL/6J male mice offered ethanol every other day during only a 4-h access period showed greater daily intake than mice offered ethanol daily for 4 h. There was a small increase in drinking with 24 h IA in C57BL/6J mice. An experiment with HDID mice and their control heterogeneous stock stock modeled closely after a published study with C57BL/6J mice (Hwa, Chu, Levinson SA et al. Persistent escalation of alcohol drinking in C57BL/6J mice with intermittent access to 20% ethanol. Alcohol Clin Exp Res 2011;35:1938-1947) showed no significant elevation with 24 h IA exposure in either sex of any genotype. Finally, a near replication of the Hwa et al. study showed modestly greater intake in C57BL/6J mice, confirming the efficacy of 24 h IA. CONCLUSION: We conclude that 4 h of IA is likely insufficient to elevate drinking in mice. The lack of effect in HDID mice and their controls further suggests that not all genotypes respond to intermittency.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Central Nervous System Depressants; Ethanol; Female; Inbred C57BL; Inbred Strains; Male; Mice; Time Factors

Introduction to the Special Issue “Pharmacotherapies for the Treatment of Alcohol Abuse and Dependence” and a Summary of Patents Targeting other Neurotransmitter Systems - Bell, Richard L.; Franklin, Kelle M.; Hauser, Sheketha R.; Zhou, Feng C. (Recent patents on CNS drug discovery, 2012)
This paper introduces the Special Section: Pharmacotherapies for the Treatment of Alcohol Abuse and Dependence and provides a summary of patents targeting neurotransmitter systems not covered in the other four chapters. The World Health Organization notes that alcoholic-type drinking results in 2.5 million deaths per year, and these deaths occur to a disproportionately greater extent among adolescents and young adults. Developing a pharmacological treatment targeting alcohol abuse and dependence is complicated by (a) the heterogeneous nature of the disease(s), (b) alcohol affecting multiple neurotransmitter and neuromodulator systems, and (c) alcohol affecting multiple organ systems which in turn influence the function of the central nervous system. Presently, the USA Federal Drug Administration has approved three pharmacotherapies for alcoholism: disulfiram, naltrexone, and acamprosate. This chapter provides a summary of the following systems, which are not covered in the accompanying chapters; alcohol and acetaldehyde metabolism, opioid, glycinergic, GABA-A, neurosteroid, dopaminergic, serotonergic, and endocannabinoid, as well as patents targeting these systems for the treatment of alcoholism. Finally, an overview is presented on the use of pharmacogenetics and pharmacogenomics in tailoring treatments for certain subpopulations of alcoholics, which is expected to continue in the future.

Neuroimmune regulation of alcohol consumption: Behavioral validation of genes obtained from genomic studies - Blednov, Yuri A.; Ponomarev, Igor; Geil, Chelsea; Bergeson, Susan; Koob, George F.; Harris, R. Adron (Addiction biology, 2012)
Analysis of mouse brain gene expression, using strains that differ in alcohol consumption, provided a number of novel candidate genes that potentially regulate alcohol consumption. We selected six genes [beta-2-microglobulin (B2m), cathepsin S (Ctss), cathepsin F (Ctsf), interleukin 1 receptor antagonist (Il1rn), CD14 molecule (Cd14) and interleukin 6 (Il6)] for behavioral validation using null mutant mice. These genes are known to be important for immune responses but were not specifically linked to alcohol consumption by previous research. Null mutant mice were tested for ethanol intake in three tests: 24 hr two-bottle choice, limited access two-bottle choice and limited access to one bottle of ethanol. Ethanol consumption and preference were reduced in all the null mutant mice in the 24 hr two-bottle choice test, the test that was the basis for selection of these genes. No major differences were observed in consumption of saccharin in the null mutant mice. Deletion of B2m, Ctss, Il1rn, Cd14 and Il6 also reduced ethanol consumption in the limited access two bottle choice test for ethanol intake; with the Il1rn and Ctss null mutants showing reduced intake in all three tests (with some variation between males and females). These results provide the most compelling evidence to date that global gene expression analysis can identify novel genetic determinants of complex behavioral traits. Specifically, they suggest a novel role for neuroimmune signaling in regulation of alcohol consumption.

Nucleus accumbens mGluR5-associated signaling regulates binge alcohol drinking under Drinking-in-the-Dark procedures - Cozzoli, Debra K.; Courson, Justin; Caruana, Amanda L.; Miller, Bailey W.; Greentree, Daniel I.; Thomspon, Andrew B.; Wroten, Melissa G.; Zhang, Ping-Wu; Xiao, Bo; Hu, Jia-Hua; Klugmann, Matthias; Metten, Pamela; et al. (Alcoholism, clinical and experimental research, 2012)
Background Alcohol increases the expression of Group 1 metabotropic glutamate receptors (mGluRs), their associated scaffolding protein Homer2, and stimulates phosphatidylinositol 3-kinase (PI3K) within the nucleus accumbens (NAC). Moreover, functional studies suggest that NAC Group 1 mGluR/Homer2/PI3K signaling may be a potential target for pharmacotherapeutic intervention in alcoholism. Methods Immunoblotting was conducted to examine the effects of alcohol consumption under Drinking-in-the-Dark (DID) procedures on Group 1 mGluR-associated proteins in C57BL/6J (B6) mice. Follow-up behavioral studies examined the importance of Group 1 mGluR/Homer2/PI3K signaling within the NAC shell for limited access alcohol drinking. Finally, immunoblotting examined whether the NAC expression of Group 1 mGluR-associated proteins is a genetic correlate of high alcohol drinking using a selectively bred high DID (HDID-1) mouse line. Results Limited access alcohol drinking under DID procedures up-regulated NAC shell Homer2 levels, concomitant with increases in mGluR5 and NR2B. Intra-NAC shell blockade of mGluR5, Homer2, or PI3K signaling, as well as transgenic disruption of the Homer binding site on mGluR5 decreased alcohol consumption in B6 mice. Moreover, transgenic disruption of the Homer binding site on mGluR5 and Homer2 deletion both prevented the attenuating effect of mGluR5 and PI3K blockade upon intake. Finally, the basal NAC shell protein expression of mGluR1 and Homer2 was increased in offspring of HDID-1 animals. Conclusions Taken together, these data further implicate Group1 mGluR signaling through Homer2 within the NAC in excessive alcohol consumption.

Protracted abstinence from distinct drugs of abuse shows regulation of a common gene network - Le Merrer, Julie; Befort, Katia; Gardon, Olivier; Filliol, Dominique; Darcq, Emmanuel; Dembele, Doulaye; Becker, Jerome A. J.; Kieffer, Brigitte L. (Addiction Biology, 2012)
Addiction is a chronic brain disorder. Prolonged abstinence from drugs of abuse involves dysphoria, high stress responsiveness and craving. The neurobiology of drug abstinence, however, is poorly understood. We previously identified a unique set of hundred mu-opioid receptor-dependent genes in the extended amygdala, a key site for hedonic and stress processing in the brain. Here we examined these candidate genes either immediately after chronic morphine, nicotine, Δ9-tetrahydrocannabinol or alcohol, or following 4 weeks of abstinence. Regulation patterns strongly differed among chronic groups. In contrast, gene regulations strikingly converged in the abstinent groups and revealed unforeseen common adaptations within a novel huntingtin-centered molecular network previously unreported in addiction research. This study demonstrates that, regardless the drug, a specific set of transcriptional regulations develops in the abstinent brain, which possibly contributes to the negative affect characterizing protracted abstinence. This transcriptional signature may represent a hallmark of drug abstinence and a unitary adaptive molecular mechanism in substance abuse disorders.
Keywords: Addictive; Amygdala; Animal; Animals; Behavior; Brain; Cluster Analysis; Disease Models; Dronabinol; Ethanol; Gene Expression; Gene Regulatory Networks; Inbred C57BL; Male; Mice; Morphine; mu; Nicotine; Opioid; Principal Component Analysis; Real-Time Polymerase Chain Reaction; Receptors; Substance Withdrawal Syndrome; Substance-Related Disorders; Temperance; time; Transcriptional Activation

Receptor subtype-dependent galanin actions on gamma-aminobutyric acidergic neurotransmission and ethanol responses in the central amygdala - Bajo, Michal; Madamba, Samuel G.; Lu, Xiaoying; Sharkey, Lisa M.; Bartfai, Tamas; Siggins, George Robert (Addiction Biology, 2012)
The neuropeptide galanin and its three receptor subtypes (GalR1-3) are expressed in the central amygdala (CeA), a brain region involved in stress- and anxiety-related behaviors, as well as alcohol dependence. Galanin also has been suggested to play a role in alcohol intake and alcohol dependence. We examined the effects of galanin in CeA slices from wild-type and knockout (KO) mice deficient of GalR2 and both GalR1 and GalR2 receptors. Galanin had dual effects on gamma-aminobutyric acid (GABA)-ergic transmission, decreasing the amplitudes of pharmacologically isolated GABAergic inhibitory postsynaptic potentials (IPSPs) in over half of CeA neurons but augmenting IPSPs in the others. The increase in IPSP size was absent after superfusion of the GalR3 antagonist SNAP 37889, whereas the IPSP depression was absent in CeA neurons of GalR1 × GalR2 double KO and GalR2 KO mice. Paired-pulse facilitation studies showed weak or infrequent effects of galanin on GABA release. Thus, galanin may act postsynaptically through GalR3 to augment GABAergic transmission in some CeA neurons, whereas GalR2 receptors likely are involved in the depression of IPSPs. Co-superfusion of ethanol, which augments IPSPs presynaptically, together with galanin caused summated effects of ethanol and galanin in those CeA neurons showing galanin-augmented IPSPs, suggesting the two agents act via different mechanisms in this population. However, in neurons showing IPSP-diminishing galanin effects, galanin blunted the ethanol effects, suggesting a preemptive effect of galanin. These findings may increase understanding of the complex cellular mechanisms that underlie the anxiety-related behavioral effects of galanin and ethanol in CeA.
Keywords: Amygdala; Animals; Anxiety; Central Nervous System Depressants; Corticotropin-Releasing Hormone; Drug Interactions; Ethanol; Evoked Potentials; GABAergic Neurons; Galanin; gamma-Aminobutyric Acid; Inbred C57BL; Indoles; Inhibitory Postsynaptic Potentials; Knockout; Male; Mice; Psychological; Receptors; Stress

Role of corticotropin-releasing factor and corticosterone in behavioral sensitization to ethanol - Pastor, Raúl; Reed, Cheryl; Meyer, Paul J.; McKinnon, Carrie; Ryabinin, Andrey E.; Phillips, Tamara J. (The Journal of Pharmacology and Experimental Therapeutics, 2012)
Neuroadaptations underlying sensitization to drugs of abuse seem to influence compulsive drug pursuit and relapse associated with addiction. Our previous data support a role for the corticotropin-releasing factor (CRF) type-1 receptor (CRF₁) in ethanol (EtOH)-induced psychomotor sensitization. CRF₁ is endogenously activated by CRF and urocortin-1. Because genetic deletion of urocortin-1 did not affect EtOH sensitization, we hypothesized that CRF is the important ligand underlying EtOH sensitization. To test this hypothesis, we used heterozygous and homozygous knockout (KO) mice, which lack one or both copies of the gene coding for CRF, and their respective wild-type controls. EtOH sensitization was normal in heterozygous, but absent in homozygous, CRF KO mice. Corticosterone (CORT) levels were drastically reduced only in CRF KO mice. Because CRF/CRF₁ initiate EtOH-induced activation of the hypothalamic-pituitary-adrenal axis, we investigated CORT effects on EtOH sensitization. The CORT synthesis inhibitor metyrapone prevented the acquisition, but not the expression, of EtOH sensitization. Exogenous CORT administration sensitized the locomotor response to a subsequent EtOH challenge; we observed, however, that the exogenous CORT levels necessary to induce sensitization to EtOH were significantly higher than those produced by EtOH treatment. Therefore, participation of CORT seems to be necessary, but not sufficient, to explain the role of CRF/CRF₁ in the acquisition of sensitization to EtOH. Extra-hypothalamic CRF/CRF₁ mechanisms are suggested to be involved in the expression of EtOH sensitization. The present results are consistent with current theories proposing a key role for CRF and CRF₁ in drug-induced neuroplasticity, dependence, and addictive behavior.
Keywords: Addictive; Animal; Animals; Behavior; Corticosterone; Corticotropin-Releasing Hormone; Ethanol; Female; Hypothalamo-Hypophyseal System; Inbred C57BL; Knockout; Male; Metyrapone; Mice; Motor Activity; Pituitary-Adrenal System; Psychomotor Disorders; Receptors; Reflex; Righting; Urocortins

RSK2 signaling in medial habenula contributes to acute morphine analgesia - Darcq, Emmanuel; Befort, Katia; Koebel, Pascale; Pannetier, Solange; Mahoney, Megan K.; Gaveriaux-Ruff, Claire; Hanauer, André; Kieffer, Brigitte L. (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2012)
It has been established that mu opioid receptors activate the ERK1/2 signaling cascade both in vitro and in vivo. The Ser/Thr kinase RSK2 is a direct downstream effector of ERK1/2 and has a role in cellular signaling, cell survival growth, and differentiation; however, its role in biological processes in vivo is less well known. Here we determined whether RSK2 contributes to mu-mediated signaling in vivo. Knockout mice for the rsk2 gene were tested for main morphine effects, including analgesia, tolerance to analgesia, locomotor activation, and sensitization to this effect, as well as morphine withdrawal. The deletion of RSK2 reduced acute morphine analgesia in the tail immersion test, indicating a role for this kinase in mu receptor-mediated nociceptive processing. All other morphine effects and adaptations to chronic morphine were unchanged. Because the mu opioid receptor and RSK2 both show high density in the habenula, we specifically downregulated RSK2 in this brain metastructure using an adeno-associated-virally mediated shRNA approach. Remarkably, morphine analgesia was significantly reduced, as observed in the total knockout animals. Together, these data indicate that RSK2 has a role in nociception, and strongly suggest that a mu opioid receptor-RSK2 signaling mechanism contributes to morphine analgesia at the level of habenula. This study opens novel perspectives for both our understanding of opioid analgesia, and the identification of signaling pathways operating in the habenular complex.
Keywords: 90-kDa; Analgesics; Analysis of Variance; Animal; Animals; Behavior; Drug Tolerance; Genetic; Habenula; Inbred C57BL; Knockout; Mice; Morphine; Morphine Dependence; Motor Activity; Naloxone; Narcotic Antagonists; Nociception; Opioid; Pain Measurement; Ribosomal Protein S6 Kinases; RNA; Signal Transduction; Small Interfering; Transduction

The small G protein H-Ras in the mesolimbic system is a molecular gateway to alcohol-seeking and excessive drinking behaviors - Ben Hamida, Sami; Neasta, Jeremie; Lasek, Amy W.; Kharazia, Viktor; Zou, Mimi; Carnicella, Sebastien; Janak, Patricia H.; Ron, Dorit (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2012)
Uncontrolled consumption of alcohol is a hallmark of alcohol abuse disorders; however, the central molecular mechanisms underlying excessive alcohol consumption are still unclear. Here, we report that the GTP binding protein, H-Ras in the nucleus accumbens (NAc) plays a key role in neuroadaptations that underlie excessive alcohol-drinking behaviors. Specifically, acute (15 min) systemic administration of alcohol (2.5 g/kg) leads to the activation of H-Ras in the NAc of mice, which is observed even 24 h later. Similarly, rat operant self-administration of alcohol (20%) also results in the activation of H-Ras in the NAc. Using the same procedures, we provide evidence suggesting that the exchange factor GRF1 is upstream of H-Ras activation by alcohol. Importantly, we show that infection of mice NAc with lentivirus expressing a short hairpin RNA that targets the H-Ras gene produces a significant reduction of voluntary consumption of 20% alcohol. In contrast, knockdown of H-Ras in the NAc of mice did not alter water, quinine, and saccharin intake. Furthermore, using two-bottle choice and operant self-administration procedures, we show that inhibiting H-Ras activity by intra-NAc infusion of the farnesyltransferase inhibitor, FTI-276, produced a robust decrease of rats' alcohol drinking; however, sucrose consumption was unaltered. Finally, intra-NAc infusion of FTI-276 also resulted in an attenuation of seeking for alcohol. Together, these results position H-Ras as a central molecular mediator of alcohol's actions within the mesolimbic system and put forward the potential value of the enzyme as a novel target to treat alcohol use disorders.
Keywords: Alcohol Drinking; Animals; Binge Drinking; Choice Behavior; Ethanol; Farnesyltranstransferase; Long-Evans; Male; Methionine; Mice; Nucleus Accumbens; Phosphorylation; Proto-Oncogene Proteins p21(ras); ras-GRF1; Rats; Sucrose; Transgenic

Stress-related neuropeptides and addictive behaviors: beyond the usual suspects - Schank, Jesse R.; Ryabinin, Andrey E.; Giardino, William J.; Ciccocioppo, Roberto; Heilig, Markus (Neuron, 2012)
Addictive disorders are chronic, relapsing conditions that cause extensive disease burden. Genetic factors partly account for susceptibility to addiction, but environmental factors such as stressful experiences and prolonged exposure of the brain to addictive drugs promote its development. Progression to addiction involves neuroadaptations within neurocircuitry that mediates stress responses and is influenced by several peptidergic neuromodulators. While corticotrophin releasing factor is the prototypic member of this class, recent work has identified several additional stress-related neuropeptides that play an important role in regulation of drug intake and relapse, including the urocortins, nociceptin, substance P, and neuropeptide S. Here, we review this emerging literature, discussing to what extent the properties of these neuromodulators are shared or distinct and considering their potential as drug targets.
Keywords: Adaptation; Addictive; Animals; Behavior; Brain; Humans; Neuropeptides; Physiological; Psychological; Stress

Transgenic over expression of nicotinic receptor alpha 5, alpha 3, and beta 4 subunit genes reduces ethanol intake in mice - Gallego, Xavier; Ruiz-Medina, Jessica; Valverde, Olga; Molas, Susanna; Robles, Noemí; Sabrià, Josefa; Crabbe, John C.; Dierssen, Mara (Alcohol (Fayetteville, N.Y.), 2012)
Abuse of alcohol and smoking are extensively co-morbid. Some studies suggest partial commonality of action of alcohol and nicotine mediated through nicotinic acetylcholine receptors (nAChRs). We tested mice with transgenic over expression of the alpha 5, alpha 3, beta 4 receptor subunit genes, which lie in a cluster on human chromosome 15, that were previously shown to have increased nicotine self-administration, for several responses to ethanol. Transgenic and wild-type mice did not differ in sensitivity to several acute behavioral responses to ethanol. However, transgenic mice drank less ethanol than wild-type in a two-bottle (ethanol vs. water) preference test. These results suggest a complex role for this receptor subunit gene cluster in the modulation of ethanol's as well as nicotine's effects.
Keywords: Alcohol Drinking; Animals; Ethanol; Humans; Locomotion; Mice; Motor Activity; Nerve Tissue Proteins; Nicotinic; Receptors; Reflex; Righting; Transgenic

Translational behaviour-genetic studies of alcohol: are we there yet? - Crabbe, J. C. (Genes, Brain, and Behavior, 2012)
In biomedical research, one key stage of translating basic science knowledge to clinical practice is the reconciliation of phenotypes employed for laboratory animal studies with those important for the clinical condition. Alcohol dependence (AD) is a prototypic complex genetic trait. There is a long history of behaviour-genetic studies of AD in both human subjects and various genetic animal models. This review assesses the state of the art in our understanding of the genetic contributions to AD. In particular, it primarily focuses on the phenotypes studied in mouse genetic animal models, comparing them to the aspects of the human condition they are intended to target. It identifies several features of AD where genetic animal models have been particularly useful, and tries to identify understudied areas where there is good promise for further genetic animal model work.
Keywords: alcoholism; Animal; Animals; Disease Models; Humans; Mice; Translational Medical Research

Understanding Alcoholism Through microRNA Signatures in Brains of Human Alcoholics - Nunez, Yury O.; Mayfield, R. Dayne (Frontiers in Genetics, 2012)
Advances in the fields of genomics and genetics in the last decade have identified a large number of genes that can potentially influence alcohol-drinking behavior in humans as well as animal models. Consequently, the task of identifying efficient molecular targets that could be used to develop effective therapeutics against the disease has become increasingly daunting. One of the reasons for this is the fact that each of the many alcohol-responsive genes only contributes a small effect to the overall mechanism and disease phenotype, as is characteristic of complex traits. Current research trends are hence shifting toward the analysis of gene networks rather than emphasizing individual genes. The discovery of microRNAs and their mechanisms of action on regulation of transcript level and protein translation have made evident the utility of these small non-coding RNA molecules that act as central coordinators of multiple cross-communicating cellular pathways. Cells exploit the fact that a single microRNA can target hundreds of mRNA transcripts and that a single mRNA transcript can be simultaneously targeted by distinct microRNAs, to ensure fine-tuned and/or redundant control over a large number of cellular functions. By the same token, we can use these properties of microRNAs to develop novel, targeted strategies to combat complex disorders. In this review, we will focus on recent discoveries of microRNA signatures in brain of human alcoholics supporting the hypothesis that changes in gene expression and regulation by microRNAs are responsible for long-term neuroadaptations occurring during development of alcoholism. We also discuss insights into the potential modulation of epigenetic regulators by a subset of microRNAs. Taken together, microRNA activity may be controlling many of the cellular mechanisms already known to be involved in the development of alcoholism, and suggests potential targets for the development of novel therapeutic interventions.
Keywords: Alcohol dependence; alcoholism; Gene Expression; human postmortem brain; miRNA; non-coding RNA

Urocortins: CRF's siblings and their potential role in anxiety, depression and alcohol drinking behavior - Ryabinin, Andrey E.; Tsoory, Michael M.; Kozicz, Tamas; Thiele, Todd E.; Neufeld-Cohen, Adi; Chen, Alon; Lowery-Gionta, Emily G.; Giardino, William J.; Kaur, Simranjit (Alcohol (Fayetteville, N.Y.), 2012)
It is widely accepted that stress, anxiety, depression and alcohol abuse-related disorders are in large part controlled by corticotropin-releasing factor (CRF) receptors. However, evidence is accumulating that some of the actions on these receptors are mediated not by CRF, but by a family of related Urocortin (Ucn) peptides Ucn1, Ucn2 and Ucn3. The initial narrow focus on CRF as the potential main player acting on CRF receptors appears outdated. Instead it is suggested that CRF and the individual Ucns act in a complementary and brain region-specific fashion to regulate anxiety-related behaviors and alcohol consumption. This review, based on a symposium held in 2011 at the research meeting on "Alcoholism and Stress" in Volterra, Italy, highlights recent evidence for regulation of these behaviors by Ucns. In studies on stress and anxiety, the roles of Ucns, and in particular Ucn1, appear more visible in experiments analyzing adaptation to stressors rather than testing basal anxiety states. Based on these studies, we propose that the contribution of Ucn1 to regulating mood follows a U-like pattern with both high and low activity of Ucn1 contributing to high anxiety states. In studies on alcohol use disorders, the CRF system appears to regulate not only dependence-induced drinking, but also binge drinking and even basal consumption of alcohol. While dependence-induced and binge drinking rely on the actions of CRF on CRFR1 receptors, alcohol consumption in models of these behaviors is inhibited by actions of Ucns on CRFR2. In contrast, alcohol preference is positively influenced by actions of Ucn1, which is capable of acting on both CRFR1 and CRFR2. Because of complex distribution of Ucns in the nervous system, advances in this field will critically depend on development of new tools allowing site-specific analyses of the roles of Ucns and CRF.
Keywords: Alcohol Drinking; alcoholism; Animals; Anxiety; Corticotropin-Releasing Hormone; Depression; Ethanol; Humans; Receptors; Urocortins

Using Genetically Engineered Animal Models in the Postgenomic Era to Understand Gene Function in Alcoholism - Reilly, Matthew T.; Harris, R. Adron; Noronha, Antonio (Alcohol Research : Current Reviews, 2012)
Over the last 50 years, researchers have made substantial progress in identifying genetic variations that underlie the complex phenotype of alcoholism. Not much is known, however, about how this genetic variation translates into altered biological function. Genetic animal models recapitulating specific characteristics of the human condition have helped elucidate gene function and the genetic basis of disease. In particular, major advances have come from the ability to manipulate genes through a variety of genetic technologies that provide an unprecedented capacity to determine gene function in the living organism and in alcohol-related behaviors. Even newer genetic-engineering technologies have given researchers the ability to control when and where a specific gene or mutation is activated or deleted, allowing investigators to narrow the role of the gene’s function to circumscribed neural pathways and across development. These technologies are important for all areas of neuroscience, and several public and private initiatives are making a new generation of genetic-engineering tools available to the scientific community at large. Finally, high-throughput “next-generation sequencing” technologies are set to rapidly increase knowledge of the genome, epigenome, and transcriptome, which, combined with genetically engineered mouse mutants, will enhance insight into biological function. All of these resources will provide deeper insight into the genetic basis of alcoholism.

Utilizing RNA-Seq data for de novo coexpression network inference - Iancu, Ovidiu D.; Kawane, Sunita; Bottomly, Daniel; Searles, Robert; Hitzemann, Robert; McWeeney, Shannon (Bioinformatics (Oxford, England), 2012)
MOTIVATION: RNA-Seq experiments have shown great potential for transcriptome profiling. While sequencing increases the level of biological detail, integrative data analysis is also important. One avenue is the construction of coexpression networks. Because the capacity of RNA-Seq data for network construction has not been previously evaluated, we constructed a coexpression network using striatal samples, derived its network properties and compared it with microarray-based networks. RESULTS: The RNA-Seq coexpression network displayed scale-free, hierarchical network structure. We detected transcripts groups (modules) with correlated profiles; modules overlap distinct ontology categories. Neuroanatomical data from the Allen Brain Atlas reveal several modules with spatial colocalization. The network was compared with microarray-derived networks; correlations from RNA-Seq data were higher, likely because greater sensitivity and dynamic range. Higher correlations result in higher network connectivity, heterogeneity and centrality. For transcripts present across platforms, network structure appeared largely preserved. From this study, we present the first RNA-Seq data de novo network inference.
Keywords: Animals; Gene Expression Profiling; Gene Regulatory Networks; Inbred C57BL; Inbred DBA; Male; Mice; Oligonucleotide Array Sequence Analysis; RNA; Sequence Analysis

The α1 Antagonist Doxazosin Alters the Behavioral Effects of Cocaine in Rats - Haile, Colin N.; Hao, Yanli; O’Malley, Patrick; Newton, Thomas F.; Kosten, Therese A. (Brain Sciences, 2012)
Medications that target norepinephrine (NE) neurotransmission alter the behavioral effects of cocaine and may be beneficial for stimulant-use disorders. We showed previously that the short-acting, α1-adrenergic antagonist, prazosin, blocked drug-induced reinstatement of cocaine-seeking in rats and doxazosin (DOX), a longer-acting α1 antagonist blocked cocaine’s subjective effects in cocaine-dependent volunteers. To further characterize DOX as a possible pharmacotherapy for cocaine dependence, we assessed its impact on the development and expression of cocaine-induced locomotor sensitization in rats. Rats (n = 6–8) were administered saline, cocaine (COC, 10 mg/kg) or DOX (0.3 or 1.0 mg/kg) alone or in combination for 5 consecutive days (development). Following 10-days of drug withdrawal, all rats were administered COC and locomotor activity was again assessed (expression). COC increased locomotor activity across days indicative of sensitization. The high dose (1.0 mg/kg), but not the low dose (0.3 mg/kg) of DOX significantly decreased the development and expression of COC sensitization. DOX alone did not differ from saline. These results are consistent with studies showing that α1 receptors are essential for the development and expression of cocaine’s behavioral effects. Results also suggest that blockade of both the development and expression of locomotor sensitization may be important characteristics of possible pharmacotherapies for cocaine dependence in humans.

Accumbens Homer2-mediated signaling: a factor contributing to mouse strain differences in alcohol drinking? - Goulding, S. P.; Obara, I.; Lominac, K. D.; Gould, A. T.; Miller, B. W.; Klugmann, M.; Szumlinski, K. K. (Genes, Brain, and Behavior, 2011)
Alcohol-induced increases in nucleus accumbens glutamate actively regulate alcohol consumption, and the alcohol responsiveness of corticoaccumbens glutamate systems relates to genetic variance in alcohol reward. Here, we extend earlier data for inbred mouse strain differences in accumbens glutamate by examining for differences in basal and alcohol-induced changes in the striatal expression of glutamate-related signaling molecules between inbred C57BL/6J and DBA2/J mice. Repeated alcohol treatment (8 × 2 g/kg) increased the expression of Group1 metabotropic glutamate receptors, the NR2a/b subunits of the N-methyl-D-aspartate receptor, Homer2a/b, as well as the activated forms of protein kinase C (PKC) epsilon and phosphoinositol-3-kinase within ventral, but not dorsal, striatum. Regardless of prior alcohol experience, C57BL/6J mice exhibited higher accumbens levels of mGluR1/5, Homer2a/b, NR2a and activated kinases vs. DBA2/J mice, whereas an alcohol-induced rise in dorsal striatum mGluR1/5 expression was observed only in C57BL/6J mice. We next employed virus-mediated gene transfer approaches to ascertain the functional relevance of the observed strain difference in accumbens Homer2 expression for B6/D2 differences in alcohol-induced glutamate sensitization, as well as alcohol preference/intake. Manipulating nucleus accumbens shell Homer2b expression actively regulated these measures in C57BL/6J mice, whereas DBA2/J mice were relatively insensitive to the neurochemical and behavioral effects of virus-mediated changes in Homer2 expression. These data support the over-arching hypothesis that augmented accumbens Homer2-mediated glutamate signaling may be an endophenotype related to genetic variance in alcohol consumption. If relevant to humans, such data pose polymorphisms affecting glutamate receptor/Homer2 signaling in the etiology of alcoholism.
Keywords: Alcohol Drinking; Animals; Blotting; Carrier Proteins; Chromatography; Corpus Striatum; Dependovirus; Genetic; Genetic Vectors; Glutamic Acid; High Pressure Liquid; Homer Scaffolding Proteins; Immunohistochemistry; Inbred C57BL; Inbred DBA; Male; Mice; Microdialysis; Nerve Tissue Proteins; Nucleus Accumbens; Phenotype; Polymorphism; Signal Transduction; Species Specificity; Western

Activation of inflammatory signaling by lipopolysaccharide produces a prolonged increase of voluntary alcohol intake in mice - Blednov, Y. A.; Benavidez, J. M.; Geil, C.; Perra, S.; Morikawa, H.; Harris, R. A. (Brain, Behavior, and Immunity, 2011)
Previous studies showed that mice with genetic predisposition for high alcohol consumption as well as human alcoholics show changes in brain expression of genes related to immune signaling. In addition, mutant mice lacking genes related to immune function show decreased alcohol consumption (Blednov et al., 2011), suggesting that immune signaling promotes alcohol consumption. To test the possibility that activation of immune signaling will increase alcohol consumption, we treated mice with lipopolysaccaride (LPS; 1mg/kg, i.p.) and tested alcohol consumption in the continuous two-bottle choice test. To take advantage of the long-lasting activation of brain immune signaling by LPS, we measured drinking beginning one week or one month after LPS treatment and continued the studies for several months. LPS produced persistent increases in alcohol consumption in C57BL/6J (B6) inbred mice, FVBxB6F1 and B6xNZBF1 hybrid mice, but not in FVB inbred mice. To determine if this effect of LPS is mediated through binding to TLR4, we tested mice lacking CD14, a key component of TLR4 signaling. These null mutants showed no increase of alcohol intake after treatment with LPS. LPS treatment decreased ethanol-conditioned taste aversion but did not alter ethanol-conditioned place preference (B6xNZBF1 mice). Electrophysiological studies of dopamine neurons in the ventral tegmental area showed that pretreatment of mice with LPS decreased the neuronal firing rate. These results suggest that activation of immune signaling promotes alcohol consumption and alters certain aspects of alcohol reward/aversion.
Keywords: Alcohol Drinking; Analysis of Variance; Animals; Choice Behavior; Conditioning (Psychology); Electrophysiology; Ethanol; Lipopolysaccharides; Mice; Neurons; Self Administration; Species Specificity

Alcohol preference drinking in a mouse line selectively bred for high drinking in the dark - Crabbe, John C.; Spence, Stephanie E.; Brown, Lauren L.; Metten, Pamela (Alcohol (Fayetteville, N.Y.), 2011)
We have selectively bred mice that reach very high blood ethanol concentrations (BECs) after drinking from a single bottle of 20% ethanol. High Drinking in the Dark (HDID-1) mice drink nearly 6g/kg ethanol in 4h and reach average BECs of more than 1.0mg/mL. Previous studies suggest that DID and two-bottle preference for 10% ethanol with continuous access are influenced by many of the same genes. We therefore asked whether HDID-1 mice would differ from the HS/Npt control stock on two-bottle preference drinking. We serially offered mice access to 3-40% ethanol in tap water versus tap water. For ethanol concentrations between 3 and 20%, HDID-1 and HS/Npt controls did not differ in two-bottle preference drinking. At the highest concentrations, the HS/Npt mice drank more than the HDID-1 mice. We also tested the same mice for preference for two concentrations each of quinine, sucrose, and saccharin. Curiously, the mice showed preference ratios (volume of tastant/total fluid drunk) of about 50% for all tastants and concentrations. Thus, neither genotype showed either preference or avoidance for any tastant after high ethanol concentrations. Therefore, we compared naive groups of HDID-1 and HS/Npt mice for tastant preference. Results from this test showed that ethanol-naive mice preferred sweet fluids and avoided quinine but the genotypes did not differ. Finally, we tested HDID-1 and HS mice for an extended period for preference for 15% ethanol versus water during a 2-h access period in the dark. After several weeks, HDID-1 mice consumed significantly more than HS. We conclude that drinking in the dark shows some genetic overlap with other tests of preference drinking, but that the degree of genetic commonality depends on the model used.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Breeding; Choice Behavior; Darkness; Disease Models; Drinking; Ethanol; Female; Inbred C57BL; Male; Mice; Quinine; Saccharin; Sucrose; Taste

CB1 Receptors Regulate Alcohol-Seeking Behavior and Alcohol Self-administration of Female Alcohol-Preferring (P) Rats - Getachew, Bruk; Hauser, Sheketha R.; Dhaher, Ronnie; Bell, Richard L.; Oster, Scott M.; McBride, William J.; Rodd, Zachary A. (Pharmacology, biochemistry, and behavior, 2011)
Rationale The endogenous cannabinoid (CB) system mediates a number of behaviors associated with drug-seeking and drug self-administration. In this study the effects of CB1 receptor manipulations on operant ethanol (EtOH) responding during EtOH-seeking, EtOH- relapse as well as on-going EtOH self-administration were determined. Methods Alcohol-preferring (P) rats were trained in 2-lever operant chambers to self-administer 15% EtOH (v/v) and water on a concurrent fixed-ratio 5 – fixed-ratio 1 (FR5-FR1) schedule of reinforcement in daily 1-hr sessions. After 10 weeks, rats underwent 7 extinction sessions, followed by 2 weeks in their home cages without access to EtOH or operant chambers. Rats were then returned to the operant chambers for testing of EtOH-seeking behavior (no EtOH present) for 4 sessions. After a week in their home cages following the EtOH-seeking test, rats were returned to the operant chambers with access to EtOH and water (relapse). Rats were then maintained in the operant chambers for daily 1-hr sessions with access to 15% EtOH and water for several weeks. Results The CB1 receptor antagonist (SR141716A), at doses of 1 and 2 mg/kg, i.p. reduced EtOH-seeking and transiently reduced EtOH self-administration during relapse and maintenance. Conversely, treatment with the CB1 receptor agonist CP, 55-940, at doses of 1 and 10 μg/kg i.p., increased EtOH-seeking and EtOH self-administration during relapse. Conclusions The results of this study demonstrate that activation of CB1 receptors are involved in regulating EtOH-seeking as well as the reinforcing effects of EtOH under relapse and on-going self-administration conditions.

Ceftriaxone, a beta-lactam antibiotic, reduces ethanol consumption in alcohol-preferring rats - Sari, Youssef; Sakai, Makiko; Weedman, Jason M.; Rebec, George V.; Bell, Richard L. (Alcohol and Alcoholism (Oxford, Oxfordshire), 2011)
AIMS: Changes in glutamatergic transmission affect many aspects of neuroplasticity associated with ethanol and drug addiction. For instance, ethanol- and drug-seeking behavior is promoted by increased glutamate transmission in key regions of the motive circuit. We hypothesized that because glutamate transporter 1 (GLT1) is responsible for the removal of most extracellular glutamate, up-regulation or activation of GLT1 would attenuate ethanol consumption. METHODS: Alcohol-preferring (P) rats were given 24 h/day concurrent access to 15 and 30% ethanol, water and food for 7 weeks. During Week 6, P rats received either 25, 50, 100 or 200 mg/kg ceftriaxone (CEF, i.p.), a β-lactam antibiotic known to elevate GLT1 expression, or a saline vehicle for five consecutive days. Water intake, ethanol consumption and body weight were measured daily for 15 days starting on Day 1 of injections. We also tested the effects of CEF (100 and 200 mg/kg, i.p.) on daily sucrose (10%) consumption as a control for motivated behavioral drinking. RESULTS: Statistical analyses revealed a significant reduction in daily ethanol, but not sucrose, consumption following CEF treatment. During the post treatment period, there was a recovery of ethanol intake across days. Dose-dependent increases in water intake were manifest concurrent with the CEF-induced decreases in ethanol intake. Nevertheless, CEF did not affect body weight. An examination of a subset of the CEF-treated ethanol-drinking rats, on the third day post CEF treatment, revealed increases in GTL1 expression levels within the prefrontal cortex and nucleus accumbens. CONCLUSIONS: These results indicate that CEF effectively reduces ethanol intake, possibly through activation of GLT1, and may be a potential therapeutic drug for alcohol addiction treatment.
Keywords: Alcohol Drinking; Animals; Anti-Bacterial Agents; Body Weight; Ceftriaxone; Central Nervous System Depressants; Dietary Sucrose; Dose-Response Relationship; Drug; Drug-Seeking Behavior; Ethanol; Glutamate Plasma Membrane Transport Proteins; Male; Rats; Sweetening Agents

Computational detection of alternative exon usage - Laderas, Ted G.; Walter, Nicole A. R.; Mooney, Michael; Vartanian, Kristina; Darakjian, Priscila; Buck, Kari; Harrington, Christina A.; Belknap, John; Hitzemann, Robert; McWeeney, Shannon K. (Frontiers in Neuroscience, 2011)
BACKGROUND: With the advent of the GeneChip Exon Arrays, it is now possible to extract "exon-level" expression estimates, allowing for detection of alternative splicing events, one of the primary mechanisms of transcript diversity. In the context of (1) a complex trait use case and (2) a human cerebellum vs. heart comparison on previously validated data, we present a transcript-based statistical model and validation framework to allow detection of alternative exon usage (AEU) between different groups. To illustrate the approach, we detect and confirm differences in exon usage in the two of the most widely studied mouse genetic models (the C57BL/6J and DBA/2J inbred strains) and in a human dataset. RESULTS: We developed a computational framework that consists of probe level annotation mapping and statistical modeling to detect putative AEU events, as well as visualization and alignment with known splice events. We show a dramatic improvement (∼25 fold) in the ability to detect these events using the appropriate annotation and statistical model which is actually specified at the transcript level, as compared with the transcript cluster/gene-level annotation used on the array. An additional component of this workflow is a probe index that allows ranking AEU candidates for validation and can aid in identification of false positives due to single nucleotide polymorphisms. DISCUSSION: Our work highlights the importance of concordance between the functional unit interrogated (e.g., gene, transcripts) and the entity (e.g., exon, probeset) within the statistical model. The framework we present is broadly applicable to other platforms (including RNAseq).
Keywords: Alternative Splicing; exon array

Deletion of the δ opioid receptor gene impairs place conditioning but preserves morphine reinforcement - Le Merrer, Julie; Plaza-Zabala, Ainhoa; Del Boca, Carolina; Matifas, Audrey; Maldonado, Rafael; Kieffer, Brigitte L. (Biological Psychiatry, 2011)
BACKGROUND: Converging experimental data indicate that δ opioid receptors contribute to mediate drug reinforcement processes. Whether their contribution reflects a role in the modulation of drug reward or an implication in conditioned learning, however, has not been explored. In the present study, we investigated the impact of δ receptor gene knockout on reinforced conditioned learning under several experimental paradigms. METHODS: We assessed the ability of δ receptor knockout mice to form drug-context associations with either morphine (appetitive)- or lithium (aversive)-induced Pavlovian place conditioning. We also examined the efficiency of morphine to serve as a positive reinforcer in these mice and their motivation to gain drug injections, with operant intravenous self-administration under fixed and progressive ratio schedules and at two different doses. RESULTS: Mutant mice showed impaired place conditioning in both appetitive and aversive conditions, indicating disrupted context-drug association. In contrast, mutant animals displayed intact acquisition of morphine self-administration and reached breaking-points comparable to control subjects. Thus, reinforcing effects of morphine and motivation to obtain the drug were maintained. CONCLUSION: Collectively, the data suggest that δ receptor activity is not involved in morphine reinforcement but facilitates place conditioning. This study reveals a novel aspect of δ opioid receptor function in addiction-related behaviors.
Keywords: Analgesics; Animal; Animals; Appetitive Behavior; Behavior; Conditioning; delta; Discrimination (Psychology); Dose-Response Relationship; Drug; Escape Reaction; Knockout; Learning Disorders; Mice; Morphine; Motivation; Operant; Opioid; Receptors; Reinforcement (Psychology); Self Administration; Space Perception; Time Factors

Dissection of corticotropin-releasing factor system involvement in locomotor sensitivity to methamphetamine - Giardino, William J.; Pastor, Raúl; Anacker, Allison M.J.; Spangler, Erika; Cote, Dawn M.; Li, Ju; Stenzel-Poore, Mary; Phillips, Tamara J.; Ryabinin, Andrey E. (Genes, brain, and behavior, 2011)
Sensitivity to the euphoric and locomotor-activating effects of drugs of abuse may contribute to risk for excessive use and addiction. Repeated administration of psychostimulants such as methamphetamine can result in neuroadaptive consequences that manifest behaviorally as a progressive escalation of locomotor activation, termed psychomotor sensitization. The present studies addressed the involvement of specific components of the corticotropin-releasing factor (CRF) system in locomotor activation and psychomotor sensitization induced by methamphetamine (1, 2 mg/kg) by utilizing pharmacological approaches, as well as a series of genetic knockout mice, each deficient for a single component of the CRF system: CRF-R1, CRF-R2, CRF, or the CRF-related peptide Urocortin 1 (Ucn1). CRF-R1 knockout mice did not differ from wild-type mice in sensitization to methamphetamine, and pharmacological blockade of CRF-R1 with CP-154,526 (15, 30 mg/kg) in DBA/2J mice did not selectively attenuate either the acquisition or expression of methamphetamine-induced sensitization. Deletion of either of the endogenous ligands of CRF-R1 (CRF, Ucn1) either enhanced, or had no effect, on methamphetamine-induced sensitization, providing further evidence against a role for CRF-R1 signaling. Interestingly, deletion of CRF-R2 attenuated methamphetamine-induced locomotor activation, elucidating a novel contribution of the CRF system to methamphetamine sensitivity, and suggesting the participation of the endogenous urocortin peptides Ucn2 and Ucn3. Immunohistochemistry for Fos was used to visualize neural activation underlying CRF-R2-dependent sensitivity to methamphetamine, identifying the basolateral and central nuclei of the amygdala as neural substrates involved in this response. Our results support further examination of CRF-R2 involvement in neural processes associated with methamphetamine addiction.

The Edinger-Westphal nucleus: a historical, structural, and functional perspective on a dichotomous terminology - Kozicz, Tamás; Bittencourt, Jackson C.; May, Paul J.; Reiner, Anton; Gamlin, Paul D. R.; Palkovits, Miklós; Horn, Anja K. E.; Toledo, Claudio A. B.; Ryabinin, Andrey E. (The Journal of Comparative Neurology, 2011)
The eponymous term nucleus of Edinger-Westphal (EW) has come to be used to describe two juxtaposed and somewhat intermingled cell groups of the midbrain that differ dramatically in their connectivity and neurochemistry. On one hand, the classically defined EW is the part of the oculomotor complex that is the source of the parasympathetic preganglionic motoneuron input to the ciliary ganglion (CG), through which it controls pupil constriction and lens accommodation. On the other hand, EW is applied to a population of centrally projecting neurons involved in sympathetic, consumptive, and stress-related functions. This terminology problem arose because the name EW has historically been applied to the most prominent cell collection above or between the somatic oculomotor nuclei (III), an assumption based on the known location of the preganglionic motoneurons in monkeys. However, in many mammals, the nucleus designated as EW is not made up of cholinergic, preganglionic motoneurons supplying the CG and instead contains neurons using peptides, such as urocortin 1, with diverse central projections. As a result, the literature has become increasingly confusing. To resolve this problem, we suggest that the term EW be supplemented with terminology based on connectivity. Specifically, we recommend that 1) the cholinergic, preganglionic neurons supplying the CG be termed the Edinger-Westphal preganglionic (EWpg) population and 2) the centrally projecting, peptidergic neurons be termed the Edinger-Westphal centrally projecting (EWcp) population. The history of this nomenclature problem and the rationale for our solutions are discussed in this review.
Keywords: Addictive; Animals; Autonomic Fibers; Behavior; Eating; Humans; Mesencephalon; Neural Pathways; Neurons; Preganglionic; Urocortins

Ethanol consumption in mice: relationships with circadian period and entrainment - Trujillo, Jennifer L.; Do, David T.; Grahame, Nicholas J.; Roberts, Amanda J.; Gorman, Michael R. (Alcohol (Fayetteville, N.Y.), 2011)
A functional connection between the circadian timing system and alcohol consumption is suggested by multiple lines of converging evidence. Ethanol consumption perturbs physiological rhythms in hormone secretion, sleep and body temperature, and conversely, genetic and environmental perturbations of the circadian system can alter alcohol intake. A fundamental property of the circadian pacemaker, the endogenous period of its cycle under free-running conditions, was previously shown to differ between selectively bred High- (HAP) and Low- (LAP) Alcohol Preferring replicate 1 mice. To test whether there is a causal relationship between circadian period and ethanol intake, we induced experimental, rather than genetic, variations in free-running period. Male inbred C57Bl/6J mice and replicate 2 male and female HAP2 and LAP2 mice were entrained to light:dark cycles of 26 h or 22 h or remained in a standard 24 h cycle. Upon discontinuation of the light:dark cycle, experimental animals exhibited longer and shorter free-running periods, respectively. Despite robust effects on circadian period and clear circadian rhythms in drinking, these manipulations failed to alter the daily ethanol intake of the inbred strain or selected lines. Likewise, driving the circadian system at long and short periods produced no change in alcohol intake. In contrast with replicate 1 HAP and LAP lines, there was no difference in free-running period between ethanol naïve HAP2 and LAP2 mice. HAP2 mice, however, were significantly more active than LAP2 mice as measured by general home-cage movement and wheel running, a motivated behavior implicating a selection effect on reward systems. Despite a marked circadian regulation of drinking behavior, the free-running and entrained period of the circadian clock does not determine daily ethanol intake.

Ethanol increases TIEG2-MAO B cell death cascade in the prefrontal cortex of ethanol-preferring rats - Ou, Xiao-Ming; Johnson, Chandra; Lu, Deyin; Johnson, Shakevia; Paul, Ian A.; Austin, Mark C.; Iyo, Abiye H.; Miguel-Hidalgo, Jose Javier; Luo, Jia; Bell, Richard L.; Grunewald, Matthew; Wang, Junming; et al. (Neurotoxicity Research, 2011)
Brain cell loss has been reported in subjects with alcoholism. However, the molecular mechanisms are unclear. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and monoamine oxidase B (MAO B) reportedly play a role in cellular dysfunction with regards to ethanol exposure. We have recently reported that GAPDH protein expression was increased in the brains of rats fed with ethanol. Furthermore, GAPDH interacts with the transcriptional activator, transforming growth factor-beta-inducible early gene 2 (TIEG2), to augment TIEG2-mediated MAO B activation, resulting in neuronal cell damage due to ethanol exposure. The current study investigates whether the TIEG2-MAO B cascade is also active in the brains of rats fed with ethanol. Ten ethanol-preferring rats were fed with a liquid diet containing ethanol, with increasing amounts of ethanol up to a final concentration of 6.4% representing a final diet containing 36% of calories for 28 days. Ten control rats were fed the liquid diet without ethanol. The expression of TIEG2 protein, MAO B mRNA levels, MAO B catalytic activity, and the levels of anti-apoptotic protein Bcl 2 and apoptotic protein caspase 3 were determined in the prefrontal cortex of the rats. Ethanol significantly increased protein levels of TIEG2, active caspase 3, MAO B mRNA and enzyme activity, but significantly decreased Bcl 2 protein expression compared to control rats. In summary, ethanol increases the TIEG2-MAO B brain cell death cascade in rat brains, suggesting that the TIEG2-MAO B pathway is a novel pathway for brain cell damage resulting from ethanol exposure, and may contribute to chronic alcohol-induced brain damage.
Keywords: Alcohol Drinking; Animals; Cell Death; Ethanol; Male; Monoamine Oxidase; Prefrontal Cortex; Random Allocation; Rats; Signal Transduction; Trans-Activators; Wistar

Ethanol Modulation of GABAergic Inhibition in Midbrain Dopamine Neurons: Implications for the Development of Alcohol-Seeking Behaviors - Theile, Jonathan W.; Gonzales, Rueben A.; Morrisett, Richard A. (Inhibitory Synaptic Plasticity, 2011)
Activation of dopaminergic (DA) neurons of the ventral tegmental area (VTA) by ethanol has been implicated in its rewarding and reinforcing effects. However, studies from our lab demonstrate that acute ethanol enhances GABA release onto VTA-DA neurons via activation of a G protein-coupled receptor, 5-HT2C, and subsequent activation of an intracellular calcium signaling pathway. Utilizing electrophysiological methods, in this chapter we present evidence which attempts to resolve the paradoxical nature of the dual excitatory and inhibitory actions of ethanol on DA neurons. Our results suggest that ethanol-excitation of VTA-DA neurons is bi-phasic and involves interplay of excitatory and inhibitory mechanisms which can fine tune the overall action of ethanol on DA neuron excitability. Overall, these results may provide insight into mechanisms underlying the development of alcohol dependence.
Keywords: Human Physiology; neurobiology; Neurosciences

Ethanol-induced changes in the expression of proteins related to neurotransmission and metabolism in different regions of the rat brain - Zahr, Natalie M.; Bell, Richard L.; Ringham, Heather N.; Sullivan, Edith V.; Witzmann, Frank A.; Pfefferbaum, Adolf (Pharmacology, Biochemistry, and Behavior, 2011)
Despite extensive description of the damaging effects of chronic alcohol exposure on brain structure, mechanistic explanations for the observed changes are just emerging. To investigate regional brain changes in protein expression levels following chronic ethanol treatment, one rat per sibling pair of male Wistar rats was exposed to intermittent (14 h/day) vaporized ethanol, the other to air for 26 weeks. At the end of 24 weeks of vapor exposure, the ethanol group had blood ethanol levels averaging 450 mg%, had not experienced a protracted (> 16 h) withdrawal from ethanol, and revealed only mild evidence of hepatic steatosis. Extracted brains were micro-dissected to isolate the prefrontal cortex (PFC), dorsal striatum (STR), corpus callosum genu (CCg), CC body (CCb), anterior vermis (AV), and anterior dorsal lateral cerebellum (ADLC) for protein analysis with two-dimensional gel electrophoresis. Expression levels for 54 protein spots were significantly different between the ethanol- and air-treated groups. Of these 54 proteins, tandem mass spectroscopy successfully identified 39 unique proteins, the levels of which were modified by ethanol treatment: 13 in the PFC, 7 in the STR, 2 in the CCg, 7 in the CCb, 7 in the AV, and 5 in the ADLC. The functions of the proteins altered by chronic ethanol exposure were predominantly associated with neurotransmitter systems in the PFC and cell metabolism in the STR. Stress response proteins were elevated only in the PFC, AV, and ADLC perhaps supporting a role for frontocerebellar circuitry disruption in alcoholism. Of the remaining proteins, some had functions associated with cytoskeletal physiology (e.g., in the CCb) and others with transcription/translation (e.g., in the ADLC). Considered collectively, all but 4 of the 39 proteins identified in the present study have been previously identified in ethanol gene- and/or protein-expression studies lending support for their role in ethanol-related brain alterations.
Keywords: Animals; Brain Chemistry; Ethanol; Gene Expression Regulation; Male; Nerve Tissue Proteins; Neural Pathways; Rats; Synaptic Transmission; Wistar

Evaluating Gene Expression in C57BL/6J and DBA/2J Mouse Striatum Using RNA-Seq and Microarrays - Bottomly, Daniel; Walter, Nicole A. R.; Hunter, Jessica Ezzell; Darakjian, Priscila; Kawane, Sunita; Buck, Kari J.; Searles, Robert P.; Mooney, Michael; McWeeney, Shannon K.; Hitzemann, Robert (PLOS ONE, 2011)
C57BL/6J (B6) and DBA/2J (D2) are two of the most commonly used inbred mouse strains in neuroscience research. However, the only currently available mouse genome is based entirely on the B6 strain sequence. Subsequently, oligonucleotide microarray probes are based solely on this B6 reference sequence, making their application for gene expression profiling comparisons across mouse strains dubious due to their allelic sequence differences, including single nucleotide polymorphisms (SNPs). The emergence of next-generation sequencing (NGS) and the RNA-Seq application provides a clear alternative to oligonucleotide arrays for detecting differential gene expression without the problems inherent to hybridization-based technologies. Using RNA-Seq, an average of 22 million short sequencing reads were generated per sample for 21 samples (10 B6 and 11 D2), and these reads were aligned to the mouse reference genome, allowing 16,183 Ensembl genes to be queried in striatum for both strains. To determine differential expression, ‘digital mRNA counting’ is applied based on reads that map to exons. The current study compares RNA-Seq (Illumina GA IIx) with two microarray platforms (Illumina MouseRef-8 v2.0 and Affymetrix MOE 430 2.0) to detect differential striatal gene expression between the B6 and D2 inbred mouse strains. We show that by using stringent data processing requirements differential expression as determined by RNA-Seq is concordant with both the Affymetrix and Illumina platforms in more instances than it is concordant with only a single platform, and that instances of discordance with respect to direction of fold change were rare. Finally, we show that additional information is gained from RNA-Seq compared to hybridization-based techniques as RNA-Seq detects more genes than either microarray platform. The majority of genes differentially expressed in RNA-Seq were only detected as present in RNA-Seq, which is important for studies with smaller effect sizes where the sensitivity of hybridization-based techniques could bias interpretation.
Keywords: Exon mapping; Gene Expression; Inbred Strains; Mammalian genomics; Microarrays; Neostriatum; RNA Folding; RNA sequencing

GABAergic transmission modulates ethanol excitation of ventral tegmental area dopamine neurons - Theile, J. W.; Morikawa, H.; Gonzales, R. A.; Morrisett, R. A. (Neuroscience, 2011)
Activation of the dopaminergic (DA) neurons of the ventral tegmental area (VTA) by ethanol has been implicated in its rewarding and reinforcing effects. We previously demonstrated that ethanol enhances GABA release onto VTA-DA neurons via activation of 5-HT2C receptors and subsequent release of calcium from intracellular stores. Here we demonstrate that excitation of VTA-DA neurons by ethanol is limited by an ethanol-enhancement in GABA release. In this study, we performed whole-cell voltage clamp recordings of miniature inhibitory postsynaptic currents (mIPSCs) and cell-attached recordings of action potential firing from VTA-DA neurons in midbrain slices from young Long Evans rats. Acute exposure to ethanol (75 mM) transiently enhanced the firing rate of VTA-DA neurons as well as the frequency of mIPSCs. Simultaneous blockade of both GABA(A) and GABA(B) receptors (Picrotoxin (75 μM) and SCH50911 (20 μM)) disinhibited VTA-DA firing rate whereas a GABA(A) agonist (muscimol, 1 μM) strongly inhibited firing rate. In the presence of picrotoxin, ethanol enhanced VTA-DA firing rate more than in the absence of picrotoxin. Additionally, a sub-maximal concentration of muscimol together with ethanol inhibited VTA-DA firing rate more than muscimol alone. DAMGO (3 μM) inhibited mIPSC frequency but did not block the ethanol-enhancement in mIPSC frequency. DAMGO (1 and 3 μM) had no effect on VTA-DA firing rate. Naltrexone (60 μM) had no effect on basal or ethanol-enhancement of mIPSC frequency. Additionally, naltrexone (20 and 60 μM) did not block the ethanol-enhancement in VTA-DA firing rate. Overall, the present results indicate that the ethanol enhancement in GABA release onto VTA-DA neurons limits the stimulatory effect of ethanol on VTA-DA neuron activity and may have implications for the rewarding properties of ethanol.
Keywords: Animal; Animals; Disease Models; dopamine; Ethanol; gamma-Aminobutyric Acid; Long-Evans; Male; Neurons; Organ Culture Techniques; Rats; Synaptic Transmission; Ventral tegmental area

Genetic ablation of delta opioid receptors in nociceptive sensory neurons increases chronic pain and abolishes opioid analgesia - Gaveriaux-Ruff, Claire; Nozaki, Chihiro; Nadal, Xavier; Hever, Xavier C.; Weibel, Raphael; Matifas, Audrey; Reiss, David; Filliol, Dominique; Nassar, Mohammed A.; Wood, John N.; Maldonado, Rafael; Kieffer, Brigitte L. (PAIN, 2011)
Opioid receptors are major actors in pain control and are broadly distributed throughout the nervous system. A major challenge in pain research is the identification of key opioid receptor populations within nociceptive pathways, which control physiological and pathological pain. In particular, the respective contribution of peripheral vs. central receptors remains unclear, and it has not been addressed by genetic approaches. To investigate the contribution of peripheral delta opioid receptors in pain control, we created conditional knockout mice where delta receptors are deleted specifically in peripheral NaV1.8-positive primary nociceptive neurons. Mutant mice showed normal pain responses to acute heat and to mechanical and formalin stimuli. In contrast, mutant animals showed a remarkable increase of mechanical allodynia under both inflammatory pain induced by complete Freund adjuvant and neuropathic pain induced by partial sciatic nerve ligation. In these 2 models, heat hyperalgesia was virtually unchanged. SNC80, a delta agonist administered either systemically (complete Freund adjuvant and sciatic nerve ligation) or into a paw (sciatic nerve ligation), reduced thermal hyperalgesia and mechanical allodynia in control mice. However, these analgesic effects were absent in conditional mutant mice. In conclusion, this study reveals the existence of delta opioid receptor-mediated mechanisms, which operate at the level of NaV1.8-positive nociceptive neurons. Delta receptors in these neurons tonically inhibit mechanical hypersensitivity in both inflammatory and neuropathic pain, and they are essential to mediate delta opioid analgesia under conditions of persistent pain. This delta receptor population represents a feasible therapeutic target to alleviate chronic pain while avoiding adverse central effects. The conditional knockout of delta-opioid receptor in primary afferent NaV1.8 neurons augmented mechanical allodynia in persistent pain models and abolished delta opioid analgesia in these models.
Keywords: Conditional gene knockout; delta; Inflammation; Neuropathy; Nociceptive pathway; Opioid receptor

Identification of genes regulated in the mouse extended amygdala by excessive ethanol drinking associated with dependence - Contet, Candice; Gardon, Olivier; Filliol, Dominique; Becker, Jérôme A. J.; Koob, George F; Kieffer, Brigitte L (Addiction biology, 2011)
Alcoholism is characterized by a progressive loss of control over ethanol intake. The purpose of this study was to identify transcriptional changes selectively associated with excessive ethanol drinking in dependent mice, as opposed to non-dependent mice maintaining a stable voluntary consumption or mice solely undergoing forced intoxication. We measured expression levels of 106 candidate genes in the extended amygdala, a key brain structure for the development of drug addiction. Cluster analysis identified 17 and 15 genes selectively induced or repressed, respectively, under conditions of excessive drinking. These genes belong to signaling pathways involved in neurotransmission and transcriptional regulation.

Impaired emotional-like behavior and serotonergic function during protracted abstinence from chronic morphine - Goeldner, Celia; Lutz, Pierre-Eric; Darcq, Emmanuel; Halter, Thomas; Clesse, Daniel; Ouagazzal, Abdel-Mouttalib; Kieffer, Brigitte L. (Biological psychiatry, 2011)
Background Opiate abuse is a chronic relapsing disorder and maintaining prolonged abstinence remains a major challenge. Protracted abstinence is characterized by lowered mood and clinical studies show elevated co-morbidity between addiction and depressive disorders. At present, their relationship remains unclear and has been little studied in animal models. Here we investigated emotional alterations during protracted abstinence, in mice with a history of chronic morphine exposure. Methods C57BL6J mice were exposed to a chronic intermittent escalating morphine regimen (20-100mg/kg). Physical dependence (naloxone-precipitated withdrawal), despair-related (tail suspension test) and social behaviors were examined after 1 or 4 weeks of abstinence. Stress hormones and forebrain bioamine levels were analyzed at the end of morphine regimen and after 4 weeks abstinence. Finally, we examined the effects of chronic fluoxetine during abstinence on morphine-induced behavioral deficits. Results Acute naloxone-induced withdrawal was clearly measurable after 1 week, and became undetectable after 4 weeks. In contrast, social and despair-related were unchanged after 1 week, but low sociability and despair-like behavior became significant after 4 weeks. Chronic morphine regimen increased both corticosterone levels and forebrain serotonin turnover, but only serotonergic activity in the dorsal raphe remained impaired after 4 weeks. Remarkably, chronic fluoxetine prevented depressive-like behavioral deficits in 4-week abstinent mice. Conclusions During protracted abstinence, the immediate consequences of morphine exposure attenuate while fluoxetine-sensitive emotional alterations strengthen with time. Our study establishes a direct link between morphine abstinence and depressive-like symptoms, and strongly suggests that serotonin dysfunction represents a main mechanism contributing to mood disorders in opiate abstinence.

In Vivo Chronic Intermittent Ethanol Exposure Reverses the Polarity of Synaptic Plasticity in the Nucleus Accumbens Shell - Jeanes, Zachary M.; Buske, Tavanna R.; Morrisett, Richard A. (The Journal of Pharmacology and Experimental Therapeutics, 2011)
Glutamatergic synaptic plasticity in the nucleus accumbens (NAc) is implicated in response to sensitization to psychomotor-stimulating agents, yet ethanol effects here are undefined. We studied the acute in vitro and in vivo effects of ethanol in medium spiny neurons from the shell NAc subregion of slices of C57BL/6 mice by using whole-cell voltage-clamp recordings of α-amino-3-hydroxy-5-methyl-isoxazole-4-propionic acid (AMPA) excitatory postsynaptic current (EPSCs). Synaptic conditioning (low-frequency stimulation with concurrent postsynaptic depolarization) reliably depressed AMPA EPSCs by nearly 30%; this accumbal long-term depression (LTD) was blocked by a nonselective N-methyl-d-aspartate (NMDA) receptor antagonist (dl-2-amino-5-phosphonovaleric acid) and a selective NMDA receptor 2B antagonist [R-(R*,S*)-α-(4-hydroxyphenyl)-β-methyl-4-(phenylmethyl)-1-piperidine propanol]. Acute ethanol exposure inhibited the depression of AMPA EPSCs differentially with increasing concentrations, but this inhibitory action of ethanol was occluded by a D1-selective dopamine receptor agonist. Ethanol dependence was elicited in C57BL/6 mice by two separate 4-day bouts of chronic intermittent ethanol (CIE) vapor exposure. When assessed 24 h after a single bout of in vivo CIE vapor exposure, NAc LTD was absent, and instead NMDA receptor-dependent synaptic potentiation [long-term potentiation (LTP)] was reliably observed. It is noteworthy that both LTP and LTD were completely absent after an extended withdrawal (72 h) after a single 3-day CIE vapor bout. These observations demonstrate that 1) accumbal synaptic depression is mediated by NR2B receptors, 2) accumbal synaptic depression is highly sensitive to both acute and chronic ethanol exposure, and 3) alterations in this synaptic process may constitute a neural adaptation that contributes to the induction and/or expression of ethanol dependence.

In vivo MRSI of hyperpolarized [1-(13)C]pyruvate metabolism in rat hepatocellular carcinoma - Darpolor, Moses M.; Yen, Yi-Fen; Chua, Mei-Sze; Xing, Lei; Clarke-Katzenberg, Regina H.; Shi, Wenfang; Mayer, Dirk; Josan, Sonal; Hurd, Ralph E.; Pfefferbaum, Adolf; Senadheera, Lasitha; So, Samuel; et al. (NMR in biomedicine, 2011)
Hepatocellular carcinoma (HCC), the primary form of human adult liver malignancy, is a highly aggressive tumor with average survival rates that are currently less than 1 year following diagnosis. Most patients with HCC are diagnosed at an advanced stage, and no efficient marker exists for the prediction of prognosis and/or response(s) to therapy. We have reported previously a high level of [1-(13)C]alanine in an orthotopic HCC using single-voxel hyperpolarized [1-(13)C]pyruvate MRS. In the present study, we implemented a three-dimensional MRSI sequence to investigate this potential hallmark of cellular metabolism in rat livers bearing HCC (n = 7 buffalo rats). In addition, quantitative real-time polymerase chain reaction was used to determine the mRNA levels of lactate dehydrogenase A, nicotinamide adenine (phosphate) dinucleotide dehydrogenase quinone 1 and alanine transaminase. The enzyme levels were significantly higher in tumor than in normal liver tissues within each rat, and were associated with the in vivo MRSI signal of [1-(13)C]alanine and [1-(13)C]lactate after a bolus intravenous injection of [1-(13)C]pyruvate. Histopathological analysis of these tumors confirmed the successful growth of HCC as a nodule in buffalo rat livers, revealing malignancy and hypervascular architecture. More importantly, the results demonstrated that the metabolic fate of [1-(13)C]pyruvate conversion to [1-(13)C]alanine significantly superseded that of [1-(13)C]pyruvate conversion to [1-(13)C]lactate, potentially serving as a marker of HCC tumors.
Keywords: Alanine; Animals; Carbon Isotopes; Carcinoma; Gene Expression Regulation; Hepatocellular; Humans; Immunohistochemistry; Lactic Acid; Liver Neoplasms; Magnetic Resonance Spectroscopy; Neoplastic; Pyruvic Acid; Rats; Reverse Transcriptase Polymerase Chain Reaction

The influence of selection for ethanol withdrawal severity on traits associated with ethanol self-administration and reinforcement - Ford, Matthew M.; Fretwell, Andrea M.; Anacker, Allison M.J.; Crabbe, John C.; Mark, Gregory P.; Finn, Deborah A. (Alcoholism, Clinical and Experimental Research, 2011)
BACKGROUND: Several meta-analyses indicate that there is an inverse genetic correlation between ethanol preference drinking and ethanol withdrawal severity, but limited work has characterized ethanol consumption in 1 genetic animal model, the Withdrawal Seizure-Prone (WSP) and-Resistant (WSR) mouse lines selected for severe or mild ethanol withdrawal, respectively. METHODS: We determined whether line differences existed in: (i) operant self-administration of ethanol during sucrose fading and under different schedules of reinforcement, followed by extinction and reinstatement of responding with conditioned cues and (ii) home cage drinking of sweetened ethanol and the development of an alcohol deprivation effect (ADE). RESULTS: Withdrawal Seizure-Prone-1 mice consumed more ethanol than WSR-1 mice under a fixed ratio (FR)-4 schedule as ethanol was faded into the sucrose solution, but this line difference dissipated as the sucrose was faded out to yield an unadulterated 10% v/v ethanol solution. In contrast, WSR-1 mice consumed more ethanol than WSP-1 mice when a schedule was imposed that procedurally separated appetitive and consummatory behaviors. After both lines achieved the extinction criterion, reinstatement was serially evaluated following oral ethanol priming, light cue presentation, and a combination of the 2 cues. The light cue produced maximal reinstatement of responding in WSP-1 mice, whereas the combined cue was required to produce maximal reinstatement of responding in WSR-1 mice. There was no line difference in the home cage consumption of a sweetened ethanol solution over a period of 1 month. Following a 2-week period of abstinence, neither line developed an ADE. CONCLUSIONS: Although some line differences in ethanol self-administration and reinstatement were identified between WSP-1 and WSR-1 mice, the absence of consistent divergence suggests that the genes underlying these behaviors do not reliably overlap with those that govern withdrawal severity.
Keywords: Alcohol Drinking; Alcohol Withdrawal Seizures; Animals; Conditioning; Extinction; Male; Mice; Motivation; Mutant Strains; Operant; Psychological; Reinforcement (Psychology); Self Administration; Substance Withdrawal Syndrome; Sucrose

Limited Access Ethanol Drinking in the Dark in Adolescent and Adult Mice - Metten, Pamela; Brown, Lauren Lyon; Crabbe, John C. (Pharmacology, biochemistry, and behavior, 2011)
Adult risk of alcohol dependence increases the younger one first engages in intoxicating consumption. Adolescent mice drink more ethanol than do adults on a g/kg basis, an increase sometimes persisting into adulthood, and this is genotype-dependent. Most studies have used 24-hr two-bottle preference, with choice between ethanol and water. We studied the developmental onset of binge drinking using limited access ethanol drinking in the dark (DID) in male and female mice. To establish age dependence in DID magnitude, we tested HS/Npt mice of 6 ages for DID for two weeks, and, when 9 weeks old, retested them for two weeks vs naïve adult controls. Age groups drank equivalently in their first week; thus, adolescent HS/Npt mice do not show greater DID than adults. Six week old mice drank more ethanol during their second week relative to their other weeks. Ethanol DID during early adolescence (4 weeks) led to increased drinking in adulthood, as did initial DID exposure at 8 weeks. High Drinking in the Dark-1 (HDID-1) mice (4, 6, 9 weeks old), selectively bred for high blood ethanol after DID, were tested for 9 weeks. Mice beginning at 4 weeks generally drank more ethanol than those of other age groups. Comparison at the same ages showed that 9 week olds initiated at 4 weeks drank more ethanol than did naïve 9 week olds, but all three groups of age-matched mice drank equivalent amounts once 10 weeks and older. The DID test is thus sensitive to developmental age. DID intakes by young adolescent HDID-1 mice were greater than by older mice, like studies with two-bottle preference. Early DID led to increased drinking as adults only in HS/Npt mice. HDID-1 mice provide a useful animal model for exploring whether DID and continuous access preference drinking have parallel consequences when initiated in adolescence.

Lmo genes regulate behavioral responses to ethanol in Drosophila melanogaster and the mouse - Lasek, Amy W.; Giorgetti, Francesco; Berger, Karen H.; Tayor, Stacy; Heberlein, Ulrike (Alcoholism, Clinical and Experimental Research, 2011)
BACKGROUND: Previous work from our laboratory demonstrated a role for the Drosophila Lim-only (dLmo) gene in regulating behavioral responses to cocaine. Herein, we examined whether dLmo influences the flies' sensitivity to ethanol's sedating effects. We also investigated whether 1 of the mammalian homologs of dLmo, Lmo3, is involved in behavioral responses to ethanol in mice. METHODS: To examine dLmo function in ethanol-induced sedation, mutant flies with reduced or increased dLmo expression were tested using the loss of righting (LOR) assay. To determine whether mouse Lmo3 regulates behavioral responses to ethanol, we generated transgenic mice expressing a short-hairpin RNA targeting Lmo3 for RNA interference-mediated knockdown by lentiviral infection of single cell embryos. Adult founder mice, expressing varying amounts of Lmo3 in the brain, were tested using ethanol loss-of-righting-reflex (LORR) and 2-bottle choice ethanol consumption assays. RESULTS: We found that in flies, reduced dLmo activity increased sensitivity to ethanol-induced sedation, whereas increased expression of dLmo led to increased resistance to ethanol-induced sedation. In mice, reduced levels of Lmo3 were correlated with increased sedation time in the LORR test and decreased ethanol consumption in the 2-bottle choice protocol. CONCLUSIONS: These data describe a novel and conserved role for Lmo genes in flies and mice in behavioral responses to ethanol. These studies also demonstrate the feasibility of rapidly translating findings from invertebrate systems to mammalian models of alcohol abuse by combining RNA interference in transgenic mice and behavioral testing.
Keywords: Adaptor Proteins; Animal; Animals; Behavior; Brain; Central Nervous System Depressants; Disease Models; Drosophila melanogaster; Drosophila Proteins; Ethanol; Female; Genotype; Green Fluorescent Proteins; Homeodomain Proteins; Hypnotics and Sedatives; Inbred C57BL; LIM Domain Proteins; Male; Mice; RNA; Signal Transducing; Small Interfering; Transgenic

Loss of ethanol conditioned taste aversion and motor stimulation in knockin mice with ethanol-insensitive α2-containing GABA(A) receptors - Blednov, Y. A.; Borghese, C. M.; McCracken, M. L.; Benavidez, J. M.; Geil, C. R.; Osterndorff-Kahanek, E.; Werner, D. F.; Iyer, S.; Swihart, A.; Harrison, N. L.; Homanics, G. E.; Harris, R. A. (The Journal of Pharmacology and Experimental Therapeutics, 2011)
GABA type A receptors (GABA(A)-Rs) are potential targets of ethanol. However, there are multiple subtypes of this receptor, and, thus far, individual subunits have not been definitively linked with specific ethanol behavioral actions. Interestingly, though, a chromosomal cluster of four GABA(A)-R subunit genes, including α2 (Gabra2), was associated with human alcoholism (Am J Hum Genet 74:705-714, 2004; Pharmacol Biochem Behav 90:95-104, 2008; J Psychiatr Res 42:184-191, 2008). The goal of our study was to determine the role of receptors containing this subunit in alcohol action. We designed an α2 subunit with serine 270 to histidine and leucine 277 to alanine mutations that was insensitive to potentiation by ethanol yet retained normal GABA sensitivity in a recombinant expression system. Knockin mice containing this mutant subunit were tested in a range of ethanol behavioral tests. These mutant mice did not develop the typical conditioned taste aversion in response to ethanol and showed complete loss of the motor stimulant effects of ethanol. Conversely, they also demonstrated changes in ethanol intake and preference in multiple tests. The knockin mice showed increased ethanol-induced hypnosis but no difference in anxiolytic effects or recovery from acute ethanol-induced motor incoordination. Overall, these studies demonstrate that the effects of ethanol at GABAergic synapses containing the α2 subunit are important for specific behavioral effects of ethanol that may be relevant to the genetic linkage of this subunit with human alcoholism.
Keywords: 129 Strain; Alcohol Drinking; Animals; Avoidance Learning; Conditioning (Psychology); Ethanol; Female; GABA-A; Gene Knock-In Techniques; Inbred C57BL; Male; Mice; Motor Activity; Receptors; Taste; Xenopus laevis

Modeling binge-like ethanol drinking by peri-adolescent and adult P rats - Bell, Richard L.; Rodd, Zachary A.; Smith, Rebecca J.; Toalston, Jamie E.; Franklin, Kelle M.; McBride, William J. (Pharmacology, Biochemistry, and Behavior, 2011)
Alcohol binge-drinking, especially among adolescents and young adults, is a serious public health concern. The present study examined ethanol binge-like drinking by peri-adolescent [postnatal days (PNDs 30-72)] and adult (PNDs 90-132) alcohol-preferring (P) rats with a drinking-in-the-dark-multiple-scheduled-access (DID-MSA) procedure used by our laboratory. Male and female P rats were provided concurrent access to 15% and 30% ethanol for three 1-h sessions across the dark cycle 5 days/week. For the 1st week, adolescent and adult female P rats consumed 3.4 and 1.6g/kg of ethanol, respectively, during the 1st hour of access, whereas for male rats the values were 3.5 and 1.1g/kg of ethanol, respectively. Adult intakes increased to ~2.0 g/kg/h and adolescent intakes decreased to ~2.5 g/kg/h across the 6 weeks of ethanol access. The daily ethanol intake of adult DID-MSA rats approximated or modestly exceeded that seen in continuous access (CA) rats or the selection criterion for P rats (≥5 g/kg/day). However, in general, the daily ethanol intake of DID-MSA peri-adolescent rats significantly exceeded that of their CA counterparts. BELs were assessed at 15-min intervals across the 3rd hour of access during the 4th week. Ethanol intake was 1.7 g/kg vs. 2.7 g/kg and BELs were 57 mg% vs. 100mg% at 15- and 60-min, respectively. Intoxication induced by DID-MSA in female P rats was assessed during the 1st vs. 4th week of ethanol access. Level of impairment did not differ between the 2 weeks (106 vs. 97 s latency to fall, 120 s criterion) and was significant (vs. naïve controls) only during the 4th week. Overall, these findings support the use of the DID-MSA procedure in rats, and underscore the presence of age- and sex-dependent effects mediating ethanol binge-like drinking in P rats.
Keywords: Age Factors; Alcohol Drinking; Animal; Animals; Disease Models; Ethanol; Female; Male; Models; Rats; Self Administration

Molecular profiles of drinking alcohol to intoxication in C57BL/6J mice - Mulligan, Megan K.; Rhodes, Justin S.; Crabbe, John C.; Mayfield, R. Dayne; Harris, R. Adron; Ponomarev, Igor (Alcoholism, Clinical and Experimental Research, 2011)
BACKGROUND: Alcohol addiction develops through a series of stages, and mechanistic studies are needed to understand the transition from initial drug use to sustained controlled alcohol consumption followed by abuse and physical dependence. The focus of this study was to examine the effects of voluntary alcohol consumption on brain gene expression profiles using a mouse model of binge drinking. The main goal was to identify alcohol-responsive genes and functional categories after a single episode of drinking to intoxication. METHODS: We used a modification of a "Drinking In the Dark" (DID) procedure (Rhodes et al., 2005) that allows mice to experience physiologically relevant amounts of alcohol in a non-stressful environment and also allows for detection of alcohol-sensitive molecular changes in a dose-dependent manner. C57BL/6J male mice were exposed to either 20% ethanol solution or water (single bottle) starting 3 hours after lights off for 4 hours and brains were harvested immediately after the drinking session. cDNA microarrays were used to assess the effects of voluntary drinking on global gene expression in 6 brain regions. We employed three statistical approaches to analyze microarray data. RESULTS: A commonly used approach that applies a strict statistical threshold identified the eight top statistically significant genes whose expression was significantly correlated with blood ethanol concentration (BEC) in one of the brain regions. We then used a systems network approach to examine brain region-specific transcriptomes and identify modules of co-expressed (correlated) genes. In each brain region, we identified alcohol-responsive modules, i.e., modules significantly enriched for genes whose expression was correlated with BEC. A functional over-representation analysis was then applied to examine the organizing principles of alcohol-responsive modules. Genes were clustered into modules according to their roles in different physiological processes, functional groups, and cell types, including blood circulation, signal transduction, cell-cell communication, and striatal neurons. Finally, a meta-analysis across all brain regions suggested a global role of increasing alcohol dose in coordination of brain blood circulation and reaction of astrocytes. CONCLUSIONS: This study showed that acute drinking resulted in small but consistent changes in brain gene expression which occurred in a dose-dependent manner. We identified both general and region-specific changes, some of which represent adaptive changes in response to increasing alcohol dose, which may play a role in alcohol-related behaviours, such as tolerance and consumption. Our systems approach allowed us to estimate the functional values of individual genes in the context of their genetic networks and formulate new refined hypotheses. An integrative analysis including other alcohol studies suggested several top candidates for functional validation, including Mt2, Gstm1, Scn4b, Prkcz, and Park7.
Keywords: Alcohol Drinking; Alcoholic Intoxication; Animal; Animals; Brain; Central Nervous System Depressants; Disease Models; Ethanol; Gene Expression; Gene Expression Profiling; Inbred C57BL; Male; Mice; Oligonucleotide Array Sequence Analysis; Principal Component Analysis

Molecular targets of alcohol action: Translational research for pharmacotherapy development and screening - Gorini, Giorgio; Bell, Richard L.; Mayfield, R. Dayne (Progress in Molecular Biology and Translational Science, 2011)
Alcohol abuse and dependence are multifaceted disorders with neurobiological, psychological, and environmental components. Research on other complex neuropsychiatric diseases suggests that genetically influenced intermediate characteristics affect the risk for heavy alcohol consumption and its consequences. Diverse therapeutic interventions can be developed through identification of reliable biomarkers for this disorder and new pharmacological targets for its treatment. Advances in the fields of genomics and proteomics offer a number of possible targets for the development of new therapeutic approaches. This brain-focused review highlights studies identifying neurobiological systems associated with these targets and possible pharmacotherapies, summarizing evidence from clinically relevant animal and human studies, as well as sketching improvements and challenges facing the fields of proteomics and genomics. Concluding thoughts on using results from these profiling technologies for medication development are also presented.
Keywords: alcoholism; Alcohols; Animals; Biomarkers; Drug Evaluation; Health Services Research; Humans; Preclinical; Translational Medical Research

Pharmacologically targeting the P2rx4 gene on maintenance and reinstatement of alcohol self-administration in rats - Kosten, Therese A. (Pharmacology, Biochemistry, and Behavior, 2011)
Genetic studies indicate that alcohol consumption associates with expression of the P2rx4 gene, a gene that codes for the P2X(4) receptor. This receptor is a subtype in the purinergic system of ligand-gated ion channels that when activated exerts excitatory effects in CNS. P2X(4) function is inhibited by alcohol and P2X(4) receptors are modulated positively by the antiparasitic agent, ivermectin. Two experiments were performed to test the ability of ivermectin to alter the behavioral effects of alcohol in rats. After alcohol exposure was achieved via the "drinking in the dark" procedure, separate groups of Sprague-Dawley rats were trained to lever press for either alcohol (10% ethanol/2% sucrose) or sucrose (3%) solutions in operant chambers. Rats were tested for maintenance of operant self-administration under a progressive ratio condition (Experiment 1) and for reinstatement of extinguished responding induced by solution presentation (Experiment 2) after ivermectin (0; 1-10mg/kg; IP) administration. Ivermectin decreased the amount of work that the animal performed to obtain reinforcers in the maintenance study, particularly in the group reinforced with alcohol, and tended to decrease reinstated lever press responding. Conditioned approach behavior (head entries) was significantly reduced by ivermectin in both experiments. Reduction in motor activity was seen during the longer maintenance sessions but not in the shorter reinstatement sessions. Results suggest some support for ivermectin-like drugs as potential treatment agents for alcohol dependence. Caution is warranted due to modest specificity on behavior reinforced by alcohol, some reduction in general activity levels, and the lack of dose-response effects.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Behavior; Conditioning; Disease Models; Ivermectin; Male; Motor Activity; Operant; Purinergic P2X4; Rats; Receptors; Self Administration; Sprague-Dawley

Prairie voles as a novel model of socially facilitated excessive drinking - Anacker, Allison M.J.; Loftis, Jennifer M.; Kaur, Simranjit; Ryabinin, Andrey E. (Addiction Biology, 2011)
Social relationships strongly affect alcohol drinking in humans. Traditional laboratory rodents do not exhibit social affiliations with specific peers, and cannot adequately model how such relationships impact drinking. The prairie vole is a socially monogamous rodent used to study social bonds. The present study tested the prairie vole as a potential model for the effects of social affiliations on alcohol drinking. Same-sex adult sibling prairie voles were paired for five days, and then either separated into individual cages, or housed in pairs. Starting at the time of separation, the voles received unlimited access to alcohol in a two-bottle choice test versus water. Pair-housed siblings exhibited higher preference for alcohol, but not saccharin, than singly housed voles. There was a significant correlation between the amount of alcohol consumed by each member of a pair when they were housed together (r = 0.79), but not when housed apart (r = 0.20). Following automated analysis of circadian patterns of fluid consumption indicating peak fluid intake before and after the dark phase, a limited access two-hour two-bottle choice procedure was established. Drinking in this procedure resulted in physiologically relevant blood ethanol concentrations and increased Fos immunoreactivity in perioculomotor urocortin containing neurons (but not in nucleus accumbens or central nucleus of the amygdala). The high ethanol preference and sensitivity to social manipulation indicate that prairie voles can serve to model social influences on excessive drinking.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Arvicolinae; Brain; Circadian Rhythm; Disease Models; Ethanol; Inbred C57BL; Male; Metabolic Clearance Rate; Mice; Neurons; Object Attachment; Proto-Oncogene Proteins c-fos; Social Facilitation; Social Isolation; Species Specificity

Preclinical studies of alcohol binge drinking - Crabbe, John C.; Harris, R. Adron; Koob, George F. (Annals of the New York Academy of Sciences, 2011)
Binge drinking is prevalent and has serious biomedical consequences. In children, adolescents, and young adults, it is a prominent risk factor for later development of alcohol-use disorders. Many preclinical models have been employed to study the genetic risks for and biomedical consequences of alcohol drinking. However, these models historically did not result in blood-alcohol concentrations (BACs) exceeding 80 mg%; this relatively modest level is the threshold that currently defines a binge session, according to the NIAAA and CDC. Nevertheless, in alcohol-dependent rodents, binge drinking has been well documented. Key neurobiological substrates localized to brain reward and stress systems have been identified. Studies of newer models of binge drinking without dependence are reviewed here. In these models, rodents, non-human primates, and flies will drink enough to reach high BACs. They often display observable signs of intoxication. The neurobiological consequences of these episodes of binge drinking without dependence are reviewed, and preliminary evidence for roles for GABA, glutamate, opioid peptides, and corticotropin releasing factor are discussed, as is the need for more work to identify the antecedents and consequences of binge drinking in both animal models and humans.
Keywords: Alcohol Drinking; Alcohol-Related Disorders; Alcoholic Intoxication; Animals; Ethanol; Humans; Students

Sequential and opposing alterations of 5-HT1A receptor function during withdrawal from chronic morphine - Lutz, Pierre-Eric; Pradhan, Amynah A.; Goeldner, Celia; Kieffer, Brigitte L. (European neuropsychopharmacology : the journal of the European College of Neuropsychopharmacology, 2011)
Addiction is a brain chronic relapsing disorder associated with emotional distress. The serotonergic system and especially the 5-HT1A receptor crucially regulate emotional behaviors both in humans and rodents. Using [35S]GTPγS autoradiography in mice, we show that 5-HT1A receptor function is enhanced by chronic morphine treatment in the medial prefrontal cortex, and decreased in dorsal raphe nucleus one week later, two regions involved in emotional processing. These molecular adaptations could contribute to the development of emotional disorders experienced by former opiate addicts.

A systems genetic analysis of alcohol drinking by mice, rats and men: influence of brain GABAergic transmission - Saba, Laura M.; Bennett, Beth; Hoffman, Paula L.; Barcomb, Kelsey; Ishii, Takao; Kechris, Katerina; Tabakoff, Boris (Neuropharmacology, 2011)
Genetic influences on the predisposition to complex behavioral or physiological traits can reflect genetic polymorphisms that lead to altered gene product function, and/or variations in gene expression levels. We have explored quantitative variations in an animal's alcohol consumption, using a genetical genomic/phenomic approach. In our studies, gene expression is correlated with amount of alcohol consumed, and genomic regions that regulate the alcohol consumption behavior and the quantitative levels of gene expression (behavioral and expression quantitative trait loci [QTL]) are determined and used as a filter to identify candidate genes predisposing the behavior. We determined QTLs for alcohol consumption using the LXS panel of recombinant inbred mice. We then identified genes that were: 1) differentially expressed between five high and five low alcohol-consuming lines or strains of mice; and 2) were physically located in, or had an expression QTL (eQTL) within the alcohol consumption QTLs. Comparison of mRNA and protein levels in brains of high and low alcohol consuming mice led us to a bioinformatic examination of potential regulation by microRNAs of an identified candidate transcript, Gnb1 (G protein beta subunit 1). We combined our current analysis with our earlier work identifying candidate genes for the alcohol consumption trait in mice, rats and humans. Our overall analysis leads us to postulate that the activity of the GABAergic system, and in particular GABA release and GABA receptor trafficking and signaling, which involves G protein function, contributes significantly to genetic variation in the predisposition to varying levels of alcohol consumption. This article is part of a Special Issue entitled 'Trends in neuropharmacology: in memory of Erminio Costa'.
Keywords: Alcohol Drinking; Animals; Brain; Central Nervous System Depressants; Ethanol; GABA; gamma-Aminobutyric Acid; Gene Expression; Genetic Predisposition to Disease; Genetic Variation; GTP-Binding Protein beta Subunits; Heritable; Humans; Inbred C57BL; Male; Mice; MicroRNAs; Phenotype; Polymorphism; Quantitative Trait; Quantitative Trait Loci; Rats; Receptors; Single Nucleotide; Synaptic Transmission

Testing the silence of mutations: Transcriptomic and behavioral studies of GABAA receptor α1 and α2 subunit knock-in mice - Harris, R A; Osterndorff-Kahanek, E; Ponomarev, I; Homanics, GE; Blednov, YA (Neuroscience letters, 2011)
Knock-in mice were constructed with mutations in the α1 (H270, A277) and α2 (H270, A277) subunits of the GABAA receptor, which resulted in receptors that lacked modulation by ethanol but retained normal responses to GABA in vitro. A key question is whether these mutant receptors also function normally in vivo. Perturbation of brain function was evaluated by gene expression profiling in the cerebral cortex and by behavioral pharmacology experiments with GABAergic drugs. Analysis of individual transcripts found only six transcripts that were changed in α1 knock-in mice and three in the α2 mutants (p < 0.05, corrected for multiple comparisons). Two transcripts that are sensitive to neuronal activity, Arc and Fos, increased about 250% in the α2 mutants, and about 50% in the α1 mutants. Behavioral effects (loss of righting reflex, rotarod) of flurazepam and pentobarbital were not different between α2 mutants and wild-type, but they were enhanced for α1 knock-in mice. These results indicate that introduction of these mutations in the α2 subunit of the GABAA receptor does not produce marked perturbation of brain function, as measured by gene expression and GABAergic behavioral responses, but the same mutations in the α1 subunit produce more pronounced changes, especially in GABAergic function.

Type 7 Adenylyl Cyclase is Involved in the Ethanol and CRF Sensitivity of GABAergic Synapses in Mouse Central Amygdala - Cruz, Maureen T.; Bajo, Michal; Maragnoli, M. Elisabetta; Tabakoff, Boris; Siggins, George R.; Roberto, Marisa (Frontiers in Neuroscience, 2011)
The GABAergic system in the central amygdala (CeA) plays a major role in ethanol dependence and in the anxiogenic response to ethanol withdrawal. Previously, we found that both ethanol and corticotropin releasing factor (CRF) increase GABAergic transmission in mouse and rat CeA neurons, in part by enhancing the release of GABA via activation of presynaptic CRF1 receptors. CRF1 receptors are coupled to the enzyme adenylyl cyclase (AC), which produces the second messenger cyclic AMP. There are nine isoforms of AC, but we recently found that CRF1 receptors in the pituitary were coupled to the Type 7 AC (AC7). Therefore, using an in vitro electrophysiological approach in brain slices, here we have investigated a possible role of the AC7 signaling pathway in ethanol and CRF effects on CeA GABAergic synapses of genetically modified mice with diminished brain Adcy7 activity (HET) compared to their littermate male wild-type (WT) mice. We found no significant differences in basal membrane properties, mean baseline amplitude of evoked GABA(A) receptor-mediated inhibitory postsynaptic potentials (IPSPs), or paired-pulse facilitation (PPF) of GABA(A)-IPSPs between HET and WT mice. In CeA neurons of WT mice, ethanol superfusion significantly augmented (by 39%) GABAA-IPSPs and decreased PPF (by 25%), suggesting increased presynaptic GABA release. However, these effects were absent in HET mice. CRF superfusion also significantly augmented IPSPs (by 38%) and decreased PPF (by 23%) in WT CeA neurons, and still elicited a significant but smaller (by 13%) increase of IPSP amplitude, but no effect on PPF, in HET mice. These electrophysiological data suggest that AC7 plays an important role in ethanol and CRF modulation of presynaptic GABA release in CeA and thus may underlie ethanol-related behaviors such as anxiety and dependence.
Keywords: alcohol; CRH; Electrophysiology; IPSPs; knock-down mouse; paired-pulse facilitation

Up-regulation of microRNAs in brain of human alcoholics - Lewohl, Joanne M.; Nunez, Yury O.; Dodd, Peter R.; Tiwari, Gayatri R.; Harris, R. Adron; Mayfield, R. Dayne (Alcoholism, Clinical and Experimental Research, 2011)
BACKGROUND: MicroRNAs (miRNAs) are small, noncoding oligonucleotides with an important role in posttranscriptional regulation of gene expression at the level of translation and mRNA degradation. Recent studies have revealed that miRNAs play important roles in a variety of biological processes, such as cell proliferation, neuronal differentiation, developmental timing, synapse function, and neurogenesis. A single miRNA can target hundreds of mRNA transcripts for either translation repression or degradation, but the function of many human miRNAs is not known. METHODS: miRNA array analysis was performed on the prefrontal cortex of 27 individual human cases (14 alcoholics and 13 matched controls). Target genes for differentially expressed miRNAs were predicted using multiple target prediction algorithms and a consensus approach, and predicted targets were matched against differentially expressed mRNAs from the same samples. Over- and under-representation analysis was performed using hypergeometric probability and z-score tests. RESULTS: Approximately 35 miRNAs were significantly up-regulated in the alcoholic group compared with controls. Target prediction showed a large degree of overlap with our published cDNA microarray data. Functional classification of the predicted target genes of the regulated miRNAs includes apoptosis, cell cycle, cell adhesion, nervous system development, and cell-cell signaling. CONCLUSIONS: These data suggest that the reduced expression of genes in human alcoholic cases may be because of the up-regulated miRNAs. Cellular processes fundamental to neuronal plasticity appear to represent major targets of the suggested miRNA regulation.
Keywords: Alcoholics; alcoholism; Apoptosis; Brain; Case-Control Studies; Cell Adhesion; Cell Cycle; Frontal Lobe; Humans; MicroRNAs; Neuronal Plasticity; Signal Transduction; Up-Regulation

Urocortin-1 within the Centrally-Projecting Edinger-Westphal Nucleus Is Critical for Ethanol Preference - Giardino, William J.; Cocking, Davelle L.; Kaur, Simranjit; Cunningham, Christopher L.; Ryabinin, Andrey E. (PLOS ONE, 2011)
Converging lines of evidence point to the involvement of neurons of the centrally projecting Edinger-Westphal nucleus (EWcp) containing the neuropeptide Urocortin-1 (Ucn1) in excessive ethanol (EtOH) intake and EtOH sensitivity. Here, we expanded these previous findings by using a continuous-access, two-bottle choice drinking paradigm (3%, 6%, and 10% EtOH vs. tap water) to compare EtOH intake and EtOH preference in Ucn1 genetic knockout (KO) and wild-type (WT) mice. Based on previous studies demonstrating that electrolytic lesion of the EWcp attenuated EtOH intake and preference in high-drinking C57BL/6J mice, we also set out to determine whether EWcp lesion would differentially alter EtOH consumption in Ucn1 KO and WT mice. Finally, we implemented well-established place conditioning procedures in KO and WT mice to determine whether Ucn1 and the corticotropin-releasing factor type-2 receptor (CRF-R2) were involved in the rewarding and aversive effects of EtOH (2 g/kg, i.p.). Results from these studies revealed that (1) genetic deletion of Ucn1 dampened EtOH preference only in mice with an intact EWcp, but not in mice that received lesion of the EWcp, (2) lesion of the EWcp dampened EtOH intake in Ucn1 KO and WT mice, but dampened EtOH preference only in WT mice expressing Ucn1, and (3) genetic deletion of Ucn1 or CRF-R2 abolished the conditioned rewarding effects of EtOH, but deletion of Ucn1 had no effect on the conditioned aversive effects of EtOH. The current findings provide strong support for the hypothesis that EWcp-Ucn1 neurons play an important role in EtOH intake, preference, and reward.
Keywords: Animal behavior; Behavioral conditioning; Biological locomotion; Ethanol; Lesions; Mice; Neurons; Surgical and invasive medical procedures

Using the PhenoGen Website for “In Silico” Analysis of Morphine-Induced Analgesia: Identifying Candidate Genes - Hoffman, Paula L.; Bennett, Beth; Saba, Laura M.; Bhave, Sanjiv V.; Carosone-Link, Phyllis J.; Hornbaker, Cheryl K.; Kechris, Katerina J.; Williams, Robert W.; Tabakoff, Boris (Addiction biology, 2011)
The identification of genes that contribute to polygenic (complex) behavioral phenotypes is a key goal of current genetic research. One approach to this goal is to combine gene expression information with genetic information, i.e., to map chromosomal regions that regulate gene expression levels. This approach has been termed “genetical genomics”, and, when used in conjunction with the identification of genomic regions (QTLs) that regulate the complex physiological trait under investigation, provides a strong basis for candidate gene discovery. In this paper, we describe the implementation of the genetical genomic/phenotypic approach to identify candidate genes for sensitivity to the analgesic effect of morphine in BXD recombinant inbred mice. Our analysis was performed “in silico”, using an online interactive resource called PhenoGen (http://phenogen.ucdenver.edu). We describe in detail the use of this resource, which identified a set of candidate genes, some of whose products regulate the cellular localization and activity of the mu opiate receptor. The results demonstrate how PhenoGen can be used to identify a novel set of genes that can be further investigated for their potential role in pain, morphine analgesia and/or morphine tolerance.

Acute withdrawal, protracted abstinence and negative affect in alcoholism: are they linked? - Heilig, Markus; Egli, Mark; Crabbe, John C.; Becker, Howard C. (Addiction Biology, 2010)
The role of withdrawal-related phenomena in the development and maintenance of alcohol addiction remains under debate. A 'self-medication' framework postulates that emotional changes are induced by a history of alcohol use, persist into abstinence, and are a major factor in maintaining alcoholism. This view initially focused on negative emotional states during early withdrawal: these are pronounced, occur in the vast majority of alcohol-dependent patients, and are characterized by depressed mood and elevated anxiety. This concept lost popularity with the realization that in most patients, these symptoms abate over 3-6 weeks of abstinence, while relapse risk persists long beyond this period. More recently, animal data have established that a prolonged history of alcohol dependence induces more subtle neuroadaptations. These confer altered emotional processing that persists long into protracted abstinence. The resulting behavioral phenotype is characterized by excessive voluntary alcohol intake and increased behavioral sensitivity to stress. Emerging human data support the clinical relevance of negative emotionality for protracted abstinence and relapse. These developments prompt a series of research questions: (1) are processes observed during acute withdrawal, while transient in nature, mechanistically related to those that remain during protracted abstinence?; (2) is susceptibility to negative emotionality in acute withdrawal in part due to heritable factors, similar to what animal models have indicated for susceptibility to physical aspects of withdrawal?; and (3) to what extent is susceptibility to negative affect that persists into protracted abstinence heritable?
Keywords: Acute Disease; Adaptation; Affect; alcoholism; Animals; Brain; Ethanol; Humans; Phenotype; Physiological; Psychological; Recurrence; Stress; Substance Withdrawal Syndrome; Temperance

Alcohol’s Effects on Brain and Behavior - Sullivan, Edith V.; Harris, R. Adron; Pfefferbaum, Adolf (Alcohol Research & Health, 2010)
Over the past 40 years, rigorous examination of brain function, structure, and attending factors through multidisciplinary research has helped identify the substrates of alcohol-related damage in the brain. One main area of this research has focused on the neuropsychological sequelae of alcoholism, which has resulted in the description of a pattern of sparing and impairment that provided an essential understanding of the functional deficits as well as of spared capabilities that could be useful in recovery. These studies have elucidated the component processes of memory, problem solving, and cognitive control, as well as visuospatial, and motor processes and their interactions with cognitive control processes. Another large area of research has focused on observable brain pathology, using increasingly sophisticated imaging technologies—progressing from pneumoencephalography to computed tomography, magnetic resonance imaging (MRI), diffusion tensor imaging, and functional MRI—that have enabled ever more detailed insight into brain structure and function. These advancements also have allowed analysis of the course of brain structural changes through periods of drinking, abstinence, and relapse.

Amygdala transcriptome and cellular mechanisms underlying stress-enhanced fear learning in a rat model of posttraumatic stress disorder - Ponomarev, Igor; Rau, Vinuta; Eger, Edmond I.; Harris, R. Adron; Fanselow, Michael S. (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2010)
Severe stress or trauma can cause permanent changes in brain circuitry, leading to dysregulation of fear responses and the development of posttraumatic stress disorder (PTSD). To date, little is known about the molecular mechanisms underlying stress-induced long-term plasticity in fear circuits. We addressed this question by using global gene expression profiling in an animal model of PTSD, stress-enhanced fear learning (SEFL). A total of 15 footshocks were used to induce SEFL and the volatile anesthetic isoflurane was used to suppress the behavioral effects of stress. Gene expression in lateral/basolateral amygdala was measured using microarrays at 3 weeks after the exposure to different combinations of shock and isoflurane. Shock produced robust effects on amygdalar transcriptome and isoflurane blocked or reversed many of the stress-induced changes. We used a modular approach to molecular profiles of shock and isoflurane and built a network of regulated genes, functional categories, and cell types that represent a mechanistic foundation of perturbation-induced plasticity in the amygdala. This analysis partitioned perturbation-induced changes in gene expression into neuron- and astrocyte-specific changes, highlighting a previously underappreciated role of astroglia in amygdalar plasticity. Many neuron-enriched genes were highly correlated with astrocyte-enriched genes, suggesting coordinated transcriptional responses to environmental challenges in these cell types. Several individual genes were validated using RT-PCR and behavioral pharmacology. This study is the first to propose specific cellular and molecular mechanisms underlying SEFL, an animal model of PTSD, and to nominate novel molecular and cellular targets with potential for therapeutic intervention in PTSD, including glycine and neuropeptide systems, chromatin remodeling, and gliotransmission.
Keywords: Amygdala; Anesthetics; Animal; Animals; Astrocytes; Brain Chemistry; Disease Models; Electric Stimulation; Fear; Gene Expression Profiling; Gene Expression Regulation; Gene Regulatory Networks; Inhalation; Isoflurane; Long-Evans; Male; Nerve Tissue Proteins; Neuronal Plasticity; Neurons; Neuropeptides; Neuropsychological Tests; Oligonucleotide Array Sequence Analysis; Post-Traumatic; Psychological; Rats; Stress; Stress Disorders

Behavioral differences between C57BL/6J x FVB/NJ and C57BL/6J x NZB/B1NJ F1 hybrid mice: relation to control of ethanol intake - Ozburn, A. R.; Harris, R. A.; Blednov, Y. A. (Behavior Genetics, 2010)
C57BL/6J x FVB/NJ F1 (B6 x FVB) mice consume more alcohol than C57BL/6J x NZB/B1NJ F1 (B6 x NZB) mice and this high alcohol consumption is stable after abstinence whereas B6 x NZB show reduced consumption, thus providing models of Sustained Alcohol Preference (SAP) and Reduced Alcohol Preference (RAP). In female hybrids, we assessed several behavioral responses to define behaviors which might predict SAP and RAP. B6 x FVB exhibited less severe ethanol-induced conditioned taste aversion and were less sensitive to ethanol-induced loss of righting reflex than B6 x NZB. Both hybrids demonstrated ethanol-induced place preference and a low ethanol withdrawal severity. We found that these hybrids differ in their sensitivity to the aversive and sedative, but not rewarding, effects of ethanol. Results of elevated plus maze, mirror chamber, and locomotor tests reveal B6 x FVB mice are less anxious and more active than B6 x NZB mice. Results obtained offer insights about factors that determine SAP and RAP in these new genetic models of alcohol consumption.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Conditioning; Crosses; Ethanol; Female; Genetic; Heterozygote; Inbred C57BL; Inbred NZB; Inbred Strains; Maze Learning; Mice; Motor Activity; Operant; Reflex; Self Administration; Species Specificity

Biological Contribution to Social Influences on Alcohol Drinking: Evidence from Animal Models - Anacker, Allison M.J.; Ryabinin, Andrey E. (International Journal of Environmental Research and Public Health, 2010)
Social factors have a tremendous influence on instances of heavy drinking and in turn impact public health. However, it is extremely difficult to assess whether this influence is only a cultural phenomenon or has biological underpinnings. Research in non-human primates demonstrates that the way individuals are brought up during early development affects their future predisposition for heavy drinking, and research in rats demonstrates that social isolation, crowding or low social ranking can lead to increased alcohol intake, while social defeat can decrease drinking. Neurotransmitter mechanisms contributing to these effects (i.e., serotonin, GABA, dopamine) have begun to be elucidated. However, these studies do not exclude the possibility that social effects on drinking occur through generalized stress responses to negative social environments. Alcohol intake can also be elevated in positive social situations, for example, in rats following an interaction with an intoxicated peer. Recent studies have also begun to adapt a new rodent species, the prairie vole, to study the role of social environment in alcohol drinking. Prairie voles demonstrate a high degree of social affiliation between individuals, and many of the neurochemical mechanisms involved in regulation of these social behaviors (for example, dopamine, central vasopressin and the corticotropin releasing factor system) are also known to be involved in regulation of alcohol intake. Naltrexone, an opioid receptor antagonist approved as a pharmacotherapy for alcoholic patients, has recently been shown to decrease both partner preference and alcohol preference in voles. These findings strongly suggest that mechanisms by which social factors influence drinking have biological roots, and can be studied using rapidly developing new animal models.

Brain injury and recovery following binge ethanol: evidence from in vivo magnetic resonance spectroscopy - Zahr, Natalie M.; Mayer, Dirk; Rohlfing, Torsten; Hasak, Michael P.; Hsu, Oliver; Vinco, Shara; Orduna, Juan; Luong, Richard; Sullivan, Edith V.; Pfefferbaum, Adolf (Biological Psychiatry, 2010)
BACKGROUND: The binge-drinking model in rodents using intragastric injections of ethanol (EtOH) for 4 days results in argyrophilic corticolimbic tissue classically interpreted as indicating irreversible neuronal degeneration. However, recent findings suggest that acquired argyrophilia can also identify injured neurons that have the potential to recover. The current in vivo magnetic resonance (MR) imaging and spectroscopy study was conducted to test the hypothesis that binge EtOH exposure would injure but not cause the death of neurons as previously ascertained postmortem. METHODS: After baseline MR scanning, 11 of 19 rats received a loading dose of 5 g/kg EtOH via oral gavage, then a maximum of 3 g/kg every 8 hours for 4 days, for a total average cumulative EtOH dose of 43 +/- 1.2 g/kg and average blood alcohol levels of 258 +/- 12 mg/dL. All animals were scanned after 4 days of gavage (post-gavage scan) with EtOH (EtOH group) or dextrose (control [Con] group) and again after 7 days of abstinence from EtOH (recovery scan). RESULTS: Tissue shrinkage at the post-gavage scan was reflected by significantly increased lateral ventricular volume in the EtOH group compared with the Con group. At the post-gavage scan, the EtOH group had lower dorsal hippocampal N-acetylaspartate and total creatine and higher choline-containing compounds than the Con group. At the recovery scan, neither ventricular volume nor metabolite levels differentiated the groups. CONCLUSIONS: Rapid recovery of ventricular volume and metabolite levels with removal of the causative agent argues for transient rather than permanent effects of a single EtOH binge episode in rats.
Keywords: alcoholism; Analysis of Variance; Animals; Aspartic Acid; Body Weight; Brain Injuries; Brain Mapping; Central Nervous System Depressants; Cerebral Ventricles; Choline; Creatine; Ethanol; Hippocampus; Magnetic Resonance Spectroscopy; Male; Oxygen; Rats; Recovery of Function; Statistics as Topic; Taurine; Time Factors; Wistar

Cerebral dynamics and metabolism of hyperpolarized [1-13C]pyruvate using time-resolved MR spectroscopic imaging - Hurd, Ralph E; Yen, Yi-Fen; Tropp, James; Pfefferbaum, Adolf; Spielman, Daniel M; Mayer, Dirk (Journal of Cerebral Blood Flow & Metabolism, 2010)
Dynamic hyperpolarized [1-13C]pyruvate metabolic imaging in the normal anesthetized rat brain is demonstrated on a clinical 3-T magnetic resonance imaging scanner. A 12-second bolus injection of hyperpolarized [1-13C]pyruvate is imaged at a 3-second temporal resolution. The observed dynamics are evaluated with regard to cerebral blood volume (CBV), flow, transport, and metabolic exchange with the cerebral lactate pool. A model for brain [1-13C]lactate, based on blood–brain transport kinetics, CBV, and the observed pyruvate dynamics is described.

Changes in Gene Expression in Regions of the Extended Amygdala of Alcohol-Preferring Rats Following Binge-Like Alcohol Drinking - McBride, William J.; Kimpel, Mark W.; Schultz, Jonathan A.; McClintick, Jeanette N.; Edenberg, Howard J.; Bell, Richard L. (Alcohol (Fayetteville, N.Y.), 2010)
The objective of this study was to determine time-course changes in gene expression within two regions of the extended amygdala following binge-like alcohol drinking by alcohol-preferring (P) rats. Adult male P rats were given 1-hr access to 15 and 30% ethanol three times daily for 8 weeks. Rats (n = 10/time point for ethanol and n = 6/time point for water) were killed by decapitation 1, 6 and 24 hr after the last drinking episode. RNA was prepared from individual micropunch samples of the nucleus accumbens shell (ACB-shell) and central nucleus of the amygdala (CeA); analyses were conducted with Affymetrix Rat 230.2 chips. Ethanol intakes were 1.5–2 g/kg for each of the 3 sessions. There were no genes that were statistically different between the ethanol and water groups at any individual time point. Therefore, an overall effect, comparing the water and ethanol groups, was determined. In the ACB-shell and CeA, there were 276 and 402 probe sets for named genes, respectively, that differed between the two groups. There were 1.5- to 3.6- fold more genes with increased than decreased expression in the ethanol drinking group, with most differences between 1.1- to 1.2-fold. Among the differences between the ethanol and water groups were several significant Biological Processes categories that were in common between the 2 regions (e.g., synaptic transmission, neurite development); however, within these categories, there were few genes in common between the two regions. Overall, the results indicate that binge-like alcohol drinking by P rats produces region-dependent changes in the expression of genes that could alter transcription, synaptic function and neuronal plasticity in the ACB-shell and CeA; within each region, different mechanisms may underlie these alterations, since there were few common ethanol-responsive genes between the ACB-shell and CeA.

A comparison of selected quantitative trait loci associated with alcohol use phenotypes in humans and mouse models - Ehlers, Cindy L.; Walter, Nicole A. R.; Dick, Danielle M.; Buck, Kari J.; Crabbe, John C. (Addiction biology, 2010)
Evidence for genetic linkage to alcohol and other substance dependence phenotypes in areas of the human and mouse genome have now been reported with some consistency across studies. However, the question remains as to whether the genes that underlie the alcohol-related behaviors seen in mice are the same as those that underlie the behaviors observed in human alcoholics. The aims of the current set of analyses were to identify a small set of alcohol-related phenotypes in humans and in mouse by which to compare quantitative trait locus (QTL) data between the species using syntenic mapping. These analyses identified that QTLs for alcohol consumption and acute and chronic alcohol withdrawal on distal mouse chromosome 1 are syntenic to a region on human chromosome 1q where a number of studies have identified QTLs for alcohol-related phenotypes. Additionally, a QTL on human chromosome 15 for alcohol dependence severity/withdrawal identified in two human studies was found to be largely syntenic with a region on mouse chromosome 9 where two groups have found QTLs for alcohol preference. In both of these cases while the QTLs were found to be syntenic the exact phenotypes between humans and mice did not necessarily overlap. These studies demonstrate how this technique might be useful in the search for genes underlying alcohol-related phenotypes in multiple species. However, these findings also suggest that trying to match exact phenotypes in humans and mice may not be necessary or even optimal for determining whether similar genes influence a range of alcohol-related behaviors between the two species.

The Complexity of Alcohol Drinking: Studies in Rodent Genetic Models - Crabbe, John C.; Phillips, Tamara J.; Belknap, John K. (Behavior Genetics, 2010)
Risk for alcohol dependence in humans has substantial genetic contributions. Successful rodent models generally attempt to address only selected features of the human diagnosis. Most such models target the phenotype of oral administration of alcohol solutions, usually consumption of or preference for an alcohol solution versus water. Data from rats and mice for more than 50 years have shown genetic influences on preference drinking and related phenotypes. This paper summarizes some key findings from that extensive literature. Much has been learned, including the genomic location and possible identity of several genes influencing preference drinking. We report new information from congenic lines confirming QTLs for drinking on mouse chromosomes 2 and 9. There are many strengths of the various phenotypic assays used to study drinking, but there are also some weaknesses. One major weakness, the lack of drinking excessively enough to become intoxicated, has recently been addressed with a new genetic animal model, mouse lines selectively bred for their high and intoxicating blood alcohol levels after a limited period of drinking in the circadian dark. We report here results from a second replicate of that selection and compare them with the first replicate.

Consilience of Rodent and Human Phenotypes Relevant for Alcohol Dependence - Crabbe, John C. (Addiction biology, 2010)

Consilient research approaches in studying gene x environment interactions in alcohol research - Sher, Kenneth J.; Dick, Danielle M.; Crabbe, John C.; Hutchison, Kent E.; O'Malley, Stephanie S.; Heath, Andrew C. (Addiction Biology, 2010)
This review article discusses the importance of identifying gene-environment interactions for understanding the etiology and course of alcohol use disorders and related conditions. A number of critical challenges are discussed, including the fact that there is no organizing typology for classifying different types of environmental exposures, many key human environmental risk factors for alcohol dependence have no clear equivalents in other species, much of the genetic variance of alcohol dependence in human is not 'alcohol specific', and the potential range of gene-environment interactions that could be considered is so vast that maintaining statistical control of Type 1 errors is a daunting task. Despite these and other challenges, there appears to be a number of promising approaches that could be taken in order to achieve consilience and ecologically valid translation between human alcohol dependence and animal models. Foremost among these is to distinguish environmental exposures that are thought to have enduring effects on alcohol use motivation (and self-regulation) from situational environmental exposures that facilitate the expression of such motivations but do not, by themselves, have enduring effects. In order to enhance consilience, various domains of human approach motivation should be considered so that relevant environmental exposures can be sampled, as well as the appropriate species to study them in (i.e. where such motivations are ecologically relevant). Foremost among these are social environments, which are central to the initiation and escalation of human alcohol consumption. The value of twin studies, human laboratory studies and pharmacogenetic studies is also highlighted.
Keywords: alcoholism; Animal; Animals; Disease Models; Environment; Gene Expression; Genotype; Humans

Corticotropin Releasing Factor–Induced Amygdala Gamma-Aminobutyric Acid Release Plays a Key Role in Alcohol Dependence - Roberto, Marisa; Cruz, Maureen T.; Gilpin, Nicholas W.; Sabino, Valentina; Schweitzer, Paul; Bajo, Michal; Cottone, Pietro; Madamba, Samuel G.; Stouffer, David G.; Zorrilla, Eric P.; Koob, George F.; Siggins, George R.; et al. (Biological psychiatry, 2010)
Background Corticotropin-releasing factor (CRF) and gamma-aminobutyric acid (GABA)ergic systems in the central amygdala (CeA) are implicated in the high-anxiety, high-drinking profile associated with ethanol dependence. Ethanol augments CeA GABA release in ethanol-naive rats and mice. Methods Using naive and ethanol-dependent rats, we compared electrophysiologic effects and interactions of CRF and ethanol on CeA GABAergic transmission, and we measured GABA dialyzate in CeA after injection of CRF1 antagonists and ethanol. We also compared mRNA expression in CeA for CRF and CRF1 using real-time polymerase chain reaction. We assessed effects of chronic treatment with a CRF1 antagonist on withdrawal-induced increases in alcohol consumption in dependent rats. Results CRF and ethanol augmented CeA GABAergic transmission in naive rats via increased GABA release. Three CRF1 receptor (CRF1) antagonists decreased basal GABAergic responses and abolished ethanol effects. Ethanol-dependent rats exhibited heightened sensitivity to CRF and CRF1 antagonists on CeA GABA release. Intra-CeA CRF1 antagonist administration reversed dependence–related elevations in GABA dialysate and blocked ethanol-induced increases in GABA dialyzate in both dependent and naive rats. Polymerase chain reaction studies indicate increased expression of CRF and CRF1 in CeA of dependent rats. Chronic CRF1 antagonist treatment blocked withdrawal-induced increases in alcohol drinking by dependent rats and tempered moderate increases in alcohol consumption by nondependent rats in intermittent testing. Conclusions These combined findings suggest a key role for specific presynaptic CRF-GABA interactions in CeA in the development and maintenance of ethanol dependence.

Dynamin-1 co-associates with native mouse brain BKCa channels: proteomics analysis of synaptic protein complexes - Gorini, Giorgio; Ponomareva, Olga; Shores, Kevin S.; Person, Maria D.; Harris, R. Adron; Mayfield, R. Dayne (FEBS letters, 2010)
In every synapse, a large number of proteins interact with other proteins in order to carry out signaling and transmission in the central nervous system. In this study, we used interaction proteomics to identify novel synaptic protein interactions in mouse cortical membranes under native conditions. Using immunoprecipitation, immunoblotting, and mass spectrometry, we identified a number of novel synaptic protein interactions involving soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), calcium-activated potassium channel (BKCa) alpha subunits, and dynamin-1. These novel interactions offer valuable insight into the protein-protein interaction network in intact synapses that could advance understanding of vesicle trafficking, release, and recycling.
Keywords: Animals; Brain; Calcium-Activated; Dynamin I; Immunoblotting; Immunoprecipitation; Male; Mass Spectrometry; Mice; Potassium Channels; Protein Binding; Proteomics; SNARE Proteins; Synapses; Vesicle-Associated Membrane Protein 2

The Endocannabinoid System Tonically Regulates Inhibitory Transmission and Depresses the Effect of Ethanol in Central Amygdala - Roberto, Marisa; Cruz, Maureen; Bajo, Michal; Siggins, George R; Parsons, Loren H; Schweitzer, Paul (Neuropsychopharmacology, 2010)
The central amygdala (CeA) has a major role in alcohol dependence and reinforcement, and behavioral and neurochemical evidence suggests a role for the endocannabinoid (eCB) system in ethanol binging and dependence. We used a slice preparation to investigate the physiological role of cannabinoids and their interaction with ethanol on inhibitory synaptic transmission in CeA. Superfusion of the cannabinoid receptor (CB1) agonist WIN55212-2 (WIN2) onto CeA neurons decreased evoked GABAA receptor-mediated inhibitory postsynaptic potentials (IPSPs) in a concentration-dependent manner, an effect prevented by the CB1 antagonists Rimonabant (SR141716, SR1) and AM251. SR1 or AM251 applied alone augmented IPSPs, revealing a tonic eCB activity that decreased inhibitory transmission in CeA. Paired-pulse analysis suggested a presynaptic CB1 mechanism. Intracellular BAPTA abolished the ability of AM251 to augment IPSPs, demonstrating the eCB-driven nature and postsynaptic origin of the tonic CB1-dependent control of GABA release. Superfusion of ethanol increased IPSPs and addition of WIN2 reversed the ethanol effect. Similarly, previous superfusion of WIN2 prevented subsequent ethanol effects on GABAergic transmission. The ethanol-induced augmentation of IPSPs was additive to CB1 blockade, ruling out a participation of CB1 in the action of acute ethanol. Our study points to an important role of CB1 in CeA in which the eCBs tonically regulate neuronal activity, and suggests a potent mechanism for modulating CeA tone during challenge with ethanol.

Ethanol action on dopaminergic neurons in the ventral tegmental area: interaction with intrinsic ion channels and neurotransmitter inputs - Morikawa, Hitoshi; Morrisett, Richard A. (International Review of Neurobiology, 2010)
The dopaminergic system originating in the midbrain ventral tegmental area (VTA) has been extensively studied over the past decades as a critical neural substrate involved in the development of alcoholism and addiction to other drugs of abuse. Accumulating evidence indicates that ethanol modulates the functional output of this system by directly affecting the firing activity of VTA dopamine neurons, whereas withdrawal from chronic ethanol exposure leads to a reduction in the functional output of these neurons. This chapter will provide an update on the mechanistic investigations of the acute ethanol action on dopamine neuron activity and the neuroadaptations/plasticities in the VTA produced by previous ethanol experience.
Keywords: Alcohol Drinking; Animals; dopamine; Humans; Ion Channels; Neurons; Neurotransmitter Agents; Ventral tegmental area

Ethanol alters endosomal recycling of human dopamine transporters - Methner, D. Nicole Riherd; Mayfield, R. Dayne (The Journal of Biological Chemistry, 2010)
Dynamic membrane trafficking of the monoamine dopamine transporter (DAT) regulates dopaminergic signaling. Various intrinsic and pharmacological modulators can alter this trafficking. Previously we have shown ethanol potentiates in vitro DAT function and increases surface expression. However, the mechanism underlying these changes is unclear. In the present study, we found ethanol directly regulates DAT function by altering endosomal recycling of the transporter. We defined ethanol action on transporter regulation by [(3)H]DA uptake functional analysis combined with biochemical and immunological assays in stably expressing DAT HEK-293 cells. Short-term ethanol exposure potentiated DAT function in a concentration-, but not time-dependent manner. This potentiation was accompanied by a parallel increase in DAT surface expression. Ethanol had no effect on function or surface localization of the ethanol-insensitive mutant (G130T DAT), suggesting a trafficking-dependent mechanism in mediating the ethanol sensitivity of the transporter. The ethanol-induced increase in DAT surface expression occurred without altering the overall size of DAT endosomal recycling pools. We found ethanol increased the DAT membrane insertion rate while having no effect on internalization of the transporter. Ethanol had no effect on the surface expression or trafficking of the endogenously expressing transferrin receptor, suggesting ethanol does not have a nonspecific effect on endosomal recycling. These results define a novel trafficking mechanism by which ethanol regulates DAT function.
Keywords: Biotinylation; Cell Membrane; Cells; Central Nervous System Depressants; Cultured; dopamine; Dopamine Plasma Membrane Transport Proteins; Endocytosis; Endosomes; Ethanol; Humans; Kidney; Protein Transport

Ethanol consumption: how should we measure it? Achieving consilience between human and animal phenotypes - Leeman, Robert F.; Heilig, Markus; Cunningham, Christopher L.; Stephens, David N.; Duka, Theodora; O'Malley, Stephanie S. (Addiction Biology, 2010)
There is only modest overlap in the most common alcohol consumption phenotypes measured in animal studies and those typically studied in humans. To address this issue, we identified a number of alcohol consumption phenotypes of importance to the field that have potential for consilience between human and animal models. These phenotypes can be broken down into three categories: (1) abstinence/the decision to drink or abstain; (2) the actual amount of alcohol consumed; and (3) heavy drinking. A number of suggestions for human and animal researchers are made in order to address these phenotypes and enhance consilience. Laboratory studies of the decision to drink or to abstain are needed in both human and animal research. In human laboratory studies, heavy or binge drinking that meets cut-offs used in epidemiological and clinical studies should be reported. Greater attention to patterns of drinking over time is needed in both animal and human studies. Individual differences pertaining to all consumption phenotypes should be addressed in animal research. Lastly, improved biomarkers need to be developed in future research for use with both humans and animals. Greater precision in estimating blood alcohol levels in the field, together with consistent measurement of breath/blood alcohol levels in human laboratory and animal studies, provides one means of achieving greater consilience of alcohol consumption phenotypes.
Keywords: alcoholism; Animal; Animals; Conditioning; Disease Models; Ethanol; Humans; Operant; Phenotype; Rats; Recurrence; Reinforcement (Psychology); Species Specificity; Surveys and Questionnaires; Temperance

Genetic diversity and striatal gene networks: focus on the heterogeneous stock-collaborative cross (HS-CC) mouse - Iancu, Ovidiu D.; Darakjian, Priscila; Walter, Nicole AR; Malmanger, Barry; Oberbeck, Denesa; Belknap, John; McWeeney, Shannon; Hitzemann, Robert (BMC Genomics, 2010)
The current study focused on the extent genetic diversity within a species (Mus musculus) affects gene co-expression network structure. To examine this issue, we have created a new mouse resource, a heterogeneous stock (HS) formed from the same eight inbred strains that have been used to create the collaborative cross (CC). The eight inbred strains capture > 90% of the genetic diversity available within the species. For contrast with the HS-CC, a C57BL/6J (B6) × DBA/2J (D2) F2 intercross and the HS4, derived from crossing the B6, D2, BALB/cJ and LP/J strains, were used. Brain (striatum) gene expression data were obtained using the Illumina Mouse WG 6.1 array, and the data sets were interrogated using a weighted gene co-expression network analysis (WGCNA).

Genome-wide gene expression analysis identifies K-ras as a regulator of alcohol intake - Repunte-Canonigo, Vez; van der Stap, Lena D.; Chen, Jihuan; Sabino, Valentina; Wagner, Ulrich; Zorrilla, Eric P.; Schumann, Gunter; Roberts, Amanda J.; Sanna, Pietro Paolo (Brain research, 2010)
Adaptations in the anterior cingulate cortex (ACC) have been implicated in alcohol and drug addiction. To identify genes that may contribute to excessive drinking, here we performed microarray analyses in laser microdissected rat ACC after a single or repeated administration of an intoxicating dose of alcohol (3g/kg). Expression of the small G protein K-ras was reduced following both single and repeated alcohol administration. We also observed that voluntary alcohol intake in K-ras heterozygous null mice (K-ras+/−) did not increased after withdrawal from repeated cycles of intermittent ethanol vapor exposure, unlike in their wild-type littermates. To identify K-ras regulated pathways, we then profiled gene expression in the ACC of K-ras+/−, heterozygous null mice for the K-ras negative regulator Nf1 (Nf1+/−) and wild-type mice following repeated administration of an intoxicating dose of alcohol. Pathway analysis showed that alcohol differentially affected various pathways in a K-ras dependent manner – some of which previously shown to be regulated by alcohol - including the insulin/PI3K pathway, the NF-kB, the phosphodiesterases (PDEs) pathway, the Jak/Stat and the adipokine signaling pathways. Altogether, the data implicate K-ras-regulated pathways in the regulation of excessive alcohol drinking after a history of dependence.

Ghrelin receptor antagonism decreases alcohol consumption and activation of perioculomotor urocortin-containing neurons - Kaur, Simranjit; Ryabinin, Andrey E. (Alcoholism, Clinical and Experimental Research, 2010)
BACKGROUND: The current therapies for alcohol abuse disorders are not effective in all patients, and continued development of pharmacotherapies is needed. One approach that has generated recent interest is the antagonism of ghrelin receptors. Ghrelin is a gut-derived peptide important in energy homeostasis and regulation of hunger. Recent studies have implicated ghrelin in alcoholism, showing altered plasma ghrelin levels in alcoholic patients as well as reduced intakes of alcohol in ghrelin receptor knockout mice and in mice treated with ghrelin receptor antagonists. The aim of this study was to determine the neuroanatomical locus/loci of the effect of ghrelin receptor antagonism on alcohol consumption using the ghrelin receptor antagonist, D-Lys3-GHRP-6. METHODS: In Experiment 1, male C57BL/6J mice were injected with saline 3 hours into the dark cycle and allowed access to 15% (v/v) ethanol or water for 2 hours in a 2-bottle choice experiment. On test day, the mice were injected with either saline or 400 nmol of the ghrelin receptor antagonist, D-Lys3-GHRP-6, and allowed to drink 15% ethanol or water for 4 hours. The preference for alcohol and alcohol intake were determined. In Experiment 2, the same procedure was followed as in Experiment 1 but mice were only allowed access to a single bottle of 20% ethanol (v/v), and alcohol intake was determined. Blood ethanol levels were analyzed, and immunohistochemistry for c-Fos was carried out to investigate changes in neural activity. To further elucidate the mechanism by which D-Lys3-GHRP-6 affects alcohol intake, in Experiment 3, the effect of D-Lys3-GHRP-6 on the neural activation induced by intraperitoneal ethanol was investigated. For the c-Fos studies, brain regions containing ghrelin receptors were analyzed, i.e. the perioculomotor urocortin population of neurons (pIIIu), the ventral tegmental area (VTA), and the arcuate nucleus (Arc). In Experiment 4, to test if blood ethanol concentrations were affected by D-Lys3-GHRP-6, blood samples were taken at 2 time-points after D-Lys3-GHRP-6 pretreatment and systemic ethanol administration. RESULTS: In Experiment 1, D-Lys3-GHRP-6 reduced preference to alcohol and in a follow-up experiment (Experiment 2) also dramatically reduced alcohol intake when compared to saline-treated mice. The resulting blood ethanol concentrations were lower in mice treated with the ghrelin receptor antagonist. Immunohistochemistry for c-Fos showed fewer immunopositive cells in the pIIIu of the antagonist-treated mice but no difference was seen in the VTA or Arc. In Experiment 3, D-Lys3-GHRP-6 reduced the induction of c-Fos by intraperitoneal ethanol in the pIIIu but had no effect in the VTA. In the Arc, there was a significant increase in the number of c-Fos immunopositive cells after D-Lys3-GHRP-6 administration, but the antagonist had no effect on ethanol-induced expression of c-Fos. D-Lys3-GHRP-6-pretreatment also did not affect the blood ethanol concentrations observed after a systemic injection of ethanol when compared to saline-pretreated mice (Experiment 4). CONCLUSIONS: These findings indicate that the action of ghrelin on the regulation of alcohol consumption may occur via the pIIIu.
Keywords: Alcohol Drinking; Animal; Animals; Arcuate Nucleus of Hypothalamus; Choice Behavior; Disease Models; Ethanol; Ghrelin; Inbred C57BL; Male; Mice; Neurons; Oculomotor Nerve; Oligopeptides; Receptors; Urocortins; Ventral tegmental area

Human and laboratory rodent low response to alcohol: is better consilience possible? - Crabbe, John C.; Bell, Richard L.; Ehlers, Cindy L. (Addiction Biology, 2010)
If people are brought into the laboratory and given alcohol, there are pronounced differences among individuals in many responses to the drug. Some participants in alcohol challenge protocols show a cluster of 'low level of responses to alcohol' determined by observing post-drinking-related changes in subjective, motor and physiological effects at a given dose level. Those individuals characterized as having low level of response (LR) to alcohol have been shown to be at increased risk for a lifetime diagnosis of alcohol dependence (AD), and this relationship between low LR and AD appears to be in part genetic. LR to alcohol is an area where achieving greater consilience between the human and the rodent phenotypes would seem to be highly likely. However, despite extensive data from both human and rodent studies, few attempts have been made to evaluate the human and animal data systematically in order to understand which aspects of LR appear to be most directly comparable across species and thus the most promising for further study. We review four general aspects of LR that could be compared between humans and laboratory animals: (1) behavioral measures of subjective intoxication; (2) body sway; (3) endocrine responses; and (4) stimulant, autonomic and electrophysiological responses. None of these aspects of LR provide completely face-valid direct comparisons across species. Nevertheless, one of the most replicated findings in humans is the low subjective response, but, as it may reflect either aversively valenced and/or positively valenced responses to alcohol as usually assessed, it is unclear which rodent responses are analogous. Stimulated heart rate appears to be consistent in animal and human studies, although at-risk subjects appear to be more rather than less sensitive to alcohol using this measure. The hormone and electrophysiological data offer strong possibilities of understanding the neurobiological mechanisms, but the rodent data in particular are rather sparse and unsystematic. Therefore, we suggest that more effort is still needed to collect data using refined measures designed to be more directly comparable in humans and animals. Additionally, the genetically mediated mechanisms underlying this endophenotype need to be characterized further across species.
Keywords: Adrenocorticotropic Hormone; alcoholism; Aldehyde Dehydrogenase; Animal; Animals; Behavior; Choice Behavior; Humans; Laboratory; Mice; Mitochondrial; Mitochondrial Proteins; Phenotype; Rats; Species Specificity

Hybrid Mice as Genetic Models of High Alcohol Consumption - Blednov, Y. A.; Ozburn, A. R.; Walker, D.; Ahmed, S.; Belknap, J. K.; Harris, R. A. (Behavior genetics, 2010)
We showed that F1 hybrid genotypes may provide a broader variety of ethanol drinking phenotypes than the inbred progenitor strains used to create the hybrids (Blednov et al. in Alcohol Clin Exp Res 29:1949–1958–2005). To extend this work, we characterized alcohol consumption as well as intake of other tastants (saccharin, quinine and sodium chloride) in five inbred strains of mice (FVB, SJL, B6, BUB, NZB) and in their reciprocal F1 hybrids with B6 (FVBxB6; B6xFVB; NZBxB6; B6xNZB; BUBxB6; B6xBUB; SJLxB6; B6xSJL). We also compared ethanol intake in these mice for several concentrations before and after two periods of abstinence. F1 hybrid mice derived from the crosses of B6 and FVB and also B6 and SJL drank higher levels of ethanol than their progenitor strains, demonstrating overdominance for two-bottle choice drinking test. The B6 and NZB hybrid showed additivity in two-bottle choice drinking, whereas the hybrid of B6 and BUB demonstrated full or complete dominance. Genealogical origin, as well as non-alcohol taste preferences (sodium chloride), predicted ethanol consumption. Mice derived from the crosses of B6 and FVB showed high sustained alcohol preference and the B6 and NZB hybrids showed reduced alcohol preference after periods of abstinence. These new genetic models offer some advantages over inbred strains because they provide high, sustained, alcohol intake, and should allow mapping of loci important for the genetic architecture of these traits.

In vivo application of sub-second spiral chemical shift imaging (CSI) to hyperpolarized 13C metabolic imaging: comparison with phase-encoded CSI - Mayer, Dirk; Yen, Yi-Fen; Levin, Yakir S.; Tropp, James; Pfefferbaum, Adolf; Hurd, Ralph E.; Spielman, Daniel M. (Journal of Magnetic Resonance (San Diego, Calif.: 1997), 2010)
A fast spiral chemical shift imaging (CSI) has been developed to address the challenge of the limited acquisition window in hyperpolarized (13)C metabolic imaging. The sequence exploits the sparsity of the spectra and prior knowledge of resonance frequencies to reduce the measurement time by undersampling the data in the spectral domain. As a consequence, multiple reconstructions are necessary for any given data set as only frequency components within a selected bandwidth are reconstructed "in-focus" while components outside that band are severely blurred ("spectral tomosynthesis"). A variable-flip-angle scheme was used for optimal use of the longitudinal magnetization. The sequence was applied to sub-second metabolic imaging of the rat in vivo after injection of hyperpolarized [1-(13)C]-pyruvate on a clinical 3T MR scanner. The comparison with conventional CSI based on phase encoding showed similar signal-to-noise ratio (SNR) and spatial resolution in metabolic maps for the substrate and its metabolic products lactate, alanine, and bicarbonate, despite a 50-fold reduction in scan time for the spiral CSI acquisition. The presented results demonstrate that dramatic reductions in scan time are feasible in hyperpolarized (13)C metabolic imaging without a penalty in SNR or spatial resolution.
Keywords: Algorithms; Animals; Carbon Isotopes; Computer-Assisted; Kidney; Magnetic Resonance Spectroscopy; Male; Pyruvic Acid; Rats; Signal Processing; Wistar

Intron 4 containing novel GABAB1 isoforms impair GABAB receptor function - Lee, Changhoon; Mayfield, R. Dayne; Harris, R. Adron (PloS One, 2010)
BACKGROUND: Gamma-aminobutyric acid type B (GABAB) receptors decrease neural activity through G protein signaling. There are two subunits, GABAB1 and GABAB2. Alternative splicing provides GABAB1 with structural and functional diversity. cDNA microarrays showed strong signals from human brain RNA using GABAB1 intron 4 region probes. Therefore, we predicted the existence of novel splice variants. METHODOLOGY/PRINCIPAL FINDINGS: Based on the probe sequence analysis, we proposed two possible splice variants, GABAB1j and GABAB1k. The existence of human GABAB1j was verified by quantitative real-time PCR, and mouse GABAB1j was found from a microarray probe set based on human GABAB1j sequence. GABAB1j open reading frames (ORF) and expression patterns are not conserved across species, and they do not have any important functional domains except sushi domains. Thus, we focused on another possible splice variant, GABAB1k. After obtaining PCR evidence for GABAB1k existence from human, mouse, and rat, it was cloned from human and mouse by PCR along with three additional isoforms, GABAB1l, GABAB1m, and GABAB1n. Their expression levels by quantitative real-time PCR are relatively low in brain although they may be expressed in specific cell types. GABAB1l and GABAB1m inhibit GABAB receptor-induced G protein-activated inwardly rectifying K(+) channel (GIRK) currents at Xenopus oocyte two-electrode voltage clamp system. CONCLUSIONS/SIGNIFICANCE: This study supports previous suggestions that intron 4 of GABAB1 gene is a frequent splicing spot across species. Like GABAB1e, GABAB1l and GABAB1m do not have transmembrane domains but have a dimerization motif. So, they also could be secreted and bind GABAB2 dominantly instead of GABAB1a. However, only GABAB1l and GABAB1m are N- and C-terminal truncated splicing variants and impair receptor function. This suggests that the intron 4 containing N-terminal truncation is necessary for the inhibitory action of the new splice variants.
Keywords: Alternative Splicing; amino acid; Amino Acid Sequence; Animals; Brain; Dose-Response Relationship; Drug; Female; G Protein-Coupled Inwardly-Rectifying Potassium Channels; GABA-B; gamma-Aminobutyric Acid; Gene Expression Profiling; Humans; Introns; Membrane Potentials; Mice; Molecular Sequence Data; Oligonucleotide Array Sequence Analysis; Oocytes; Protein Isoforms; Rats; Receptors; Sequence Homology; Xenopus

Measurement of serum, liver, and brain cytokine induction, thiamine levels, and hepatopathology in rats exposed to a 4-day alcohol binge protocol - Zahr, Natalie M.; Luong, Richard; Sullivan, Edith V.; Pfefferbaum, Adolf (Alcoholism, Clinical and Experimental Research, 2010)
BACKGROUND: In rodent and human studies, ethanol (EtOH) exposure is associated with elevated brain levels of the magnetic resonance spectroscopy (MRS) signal representing choline-containing compounds (Cho). One interpretation of elevated brain Cho is that it is a marker of neuroinflammation, and some evidence suggests that EtOH exposure promotes neuroinflammation. This study aimed to determine whether binge EtOH exposure (intragastric 3 g/kg 25% EtOH every 8 hours for 4 days) would induce the expression of certain cytokines in blood, liver, or brain, thereby supporting the neuroinflammation hypothesis of elevated Cho. METHODS: Ten of 18 wild-type male Wistar rats (~322 g at baseline) were exposed to EtOH and attained average blood alcohol levels of ~315 mg/dl across 4 days. Blood for cytokine immunoassays was collected at baseline, after 5 doses of EtOH (binge), and immediately preceding euthanasia either 4 or 24 hours after the last dose of EtOH. Blood was additionally assayed for the levels of thiamine and liver enzymes; liver histopathology was performed postmortem; and tissue from liver and 6 brain regions was assayed for the potential induction of 7 cytokines. RESULTS: There were no group effects on the levels of thiamine or its phosphate derivatives, thiamine monophosphate or thiamine diphosphate. ANOVAs of liver enzyme levels indicated that only alkaline phosphatase (ALP) levels were higher in the EtOH group than in control group at binge; ALP elevations, however, are difficult to explain in the absence of changes in the levels of additional liver enzymes. Postmortem liver pathology provided evidence for minimal microvesicular lipidosis and portocentric fibrosis in the EtOH group. Group effects on the levels of the measured cytokines in the blood (TNF-α, IFN-γ, IL-1β, IL-4, IL-5, IL-13, and GRO/CXCL1) were not significant. Similarly, postmortem evaluation of liver cytokines did not reveal group effects. Postmortem evaluation of the 7 cytokines in 6 brain regions (anterior cerebellar vermis, cingulate cortex, frontal cortex, hippocampus, hypothalamus, striatum) also failed to identify group effects. CONCLUSIONS: A single 4-day bout of binge EtOH exposure alone was insufficient to induce the expression of 7 cytokines in blood, liver, or 6 brain regions of wild-type Wistar rats. Alternative interpretations for elevations in brain Cho in response to a 4-day binge EtOH treatment are therefore necessary and may include induction of cytokines not measured herein or other noninflammatory mechanisms.
Keywords: alcoholism; Alkaline Phosphatase; Animal; Animals; Behavior; Body Weight; Brain Chemistry; Chemical and Drug Induced Liver Injury; Cytokines; Liver; Liver Function Tests; Magnetic Resonance Spectroscopy; Male; Rats; Substance Withdrawal Syndrome; Thiamine; Wistar

Metabolic imaging in the anesthetized rat brain using hyperpolarized [1-13C] pyruvate and [1-13C] ethyl pyruvate - Hurd, Ralph E.; Yen, Yi-Fen; Mayer, Dirk; Chen, Albert; Wilson, David; Kohler, Susan; Bok, Robert; Vigneron, Daniel; Kurhanewicz, John; Tropp, James; Spielman, Daniel; Pfefferbaum, Adolf (Magnetic Resonance in Medicine, 2010)
Formulation, polarization, and dissolution conditions were developed to obtain a stable hyperpolarized solution of [1-(13)C]-ethyl pyruvate. A maximum tolerated concentration and injection rate were determined, and (13)C spectroscopic imaging was used to compare the uptake of hyperpolarized [1-(13)C]-ethyl pyruvate relative to hyperpolarized [1-(13)C]-pyruvate into anesthetized rat brain. Hyperpolarized [1-(13)C]-ethyl pyruvate and [1-(13)C]-pyruvate metabolic imaging in normal brain is demonstrated and quantified in this feasibility and range-finding study.
Keywords: Anesthetics; Animals; Brain; Carbon Isotopes; General; Magnetic Resonance Spectroscopy; Male; Pyruvates; Pyruvic Acid; Rats; Tissue Distribution; Wistar

A method for mapping intralocus interactions influencing excessive alcohol drinking - Phillips, Tamara J.; Reed, Cheryl; Burkhart-Kasch, Sue; Li, Na; Hitzemann, Robert; Yu, Chia-Hua; Brown, Lauren L.; Helms, Melinda L.; Crabbe, John C.; Belknap, John K. (Mammalian Genome: Official Journal of the International Mammalian Genome Society, 2010)
Excessive alcohol (ethanol) consumption is the hallmark of alcohol use disorders. The F1 hybrid cross between the C57BL/6J (B6) and FVB/NJ (FVB) inbred mouse strains consumes more ethanol than either progenitor strain. The purpose of this study was to utilize ethanol-drinking data and genetic information to map genes that result in overdominant (or heterotic) ethanol drinking. About 600 B6 x FVB F2 mice, half of each sex, were tested for ethanol intake and preference in a 24-h, two-bottle water versus ethanol choice procedure, with ascending ethanol concentrations. They were then tested for ethanol intake in a Drinking in the Dark (DID) procedure, first when there was no water choice and then when ethanol was offered versus water. DNA samples were obtained and genome-wide QTL analyses were performed to search for single QTLs (both additive and dominance effects) and interactions between pairs of QTLs, or epistasis. On average, F2 mice consumed excessive amounts of ethanol in the 24-h choice procedure, consistent with high levels of consumption seen in the F1 cross. Consumption in the DID procedure was similar or higher than amounts reported previously for the B6 progenitor. QTLs resulting in heightened consumption in heterozygous compared to homozygous animals were found on Chrs 11, 15, and 16 for 24-h choice 30% ethanol consumption, and on Chr 11 for DID. No evidence was found for epistasis between any pair of significant or suggestive QTLs. This indicates that the hybrid overdominance is due to intralocus interactions at the level of individual QTL.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Behavior; Choice Behavior; Chromosome Mapping; Crosses; Darkness; Epistasis; Female; Genetic; Genetic Loci; Inbred C57BL; Inbred Strains; Male; Mice; Phenotype; Quantitative Trait Loci

Mice lacking Gad2 show altered behavioral effects of ethanol, flurazepam and gabaxadol - Blednov, Yuri A.; Walker, Danielle L.; Iyer, Sangeetha V.; Homanics, Gregg; Harris, Adron R. (Addiction Biology, 2010)
Gamma-aminobutyric acid (GABA) is synthesized in brain by two isoforms of glutamic acid decarboxylase (Gad), Gad1 and Gad2. Gad1 provides most of the GABA in brain, but Gad2 can be rapidly activated in times of high GABA demand. Mice lacking Gad2 are viable whereas deletion of Gad1 is lethal. We produced null mutant mice for Gad2 on three different genetic backgrounds: predominantly C57BL/6J and one or two generations of backcrossing to 129S1/SvimJ (129N1, 129N2). We used these mice to determine if actions of alcohol are regulated by synthesis of GABA from this isoform. We also studied behavioral responses to a benzodiazepine (flurazepam) and a GABAA receptor agonist (gabaxadol). Deletion of Gad2 increased ethanol palatability and intake and slightly reduced the severity of ethanol-induced withdrawal, but these effects depended strongly on genetic background. Mutant mice on the 129N2 background showed the above three ethanol behavioral phenotypes, but the C57BL/6J inbred background did not show any of these phenotypes. Effects on ethanol consumption also depended on the test as the mutation did not alter consumption in limited access models. Deletion of Gad2 reduced the effect of flurazepam on motor incoordination and increased the effect of extrasynaptic GABAA receptor agonist gabaxadol without changing the duration of loss of righting reflex produced by these drugs. These results are consistent with earlier proposals that deletion of Gad2 (on 129N2 background) reduces synaptic GABA but also suggest changes in extrasynaptic receptor function.
Keywords: Alcohol Drinking; Alcohol Withdrawal Delirium; Animals; Benzodiazepines; Brain; Crosses; Ethanol; Flurazepam; GABA Agonists; Genetic; Genotype; Glutamate Decarboxylase; Inbred C57BL; Inbred Strains; Isoxazoles; Knockout; Male; Mice; Motor Skills; Neurologic Mutants; Phenotype; Postural Balance; Species Specificity; Taste

Mice lacking Gad2 show altered behavioral effects of ethanol, flurazepam and gabaxadol - Blednov, Yuri A.; Walker, Danielle L.; Iyer, Sangeetha V.; Homanics, Gregg; Harris, Adron R. (Addiction Biology, 2010)
Gamma-aminobutyric acid (GABA) is synthesized in brain by two isoforms of glutamic acid decarboxylase (Gad), Gad1 and Gad2. Gad1 provides most of the GABA in brain, but Gad2 can be rapidly activated in times of high GABA demand. Mice lacking Gad2 are viable whereas deletion of Gad1 is lethal. We produced null mutant mice for Gad2 on three different genetic backgrounds: predominantly C57BL/6J and one or two generations of backcrossing to 129S1/SvimJ (129N1, 129N2). We used these mice to determine if actions of alcohol are regulated by synthesis of GABA from this isoform. We also studied behavioral responses to a benzodiazepine (flurazepam) and a GABAA receptor agonist (gabaxadol). Deletion of Gad2 increased ethanol palatability and intake and slightly reduced the severity of ethanol-induced withdrawal, but these effects depended strongly on genetic background. Mutant mice on the 129N2 background showed the above three ethanol behavioral phenotypes, but the C57BL/6J inbred background did not show any of these phenotypes. Effects on ethanol consumption also depended on the test as the mutation did not alter consumption in limited access models. Deletion of Gad2 reduced the effect of flurazepam on motor incoordination and increased the effect of extrasynaptic GABAA receptor agonist gabaxadol without changing the duration of loss of righting reflex produced by these drugs. These results are consistent with earlier proposals that deletion of Gad2 (on 129N2 background) reduces synaptic GABA but also suggest changes in extrasynaptic receptor function.
Keywords: Alcohol Drinking; Alcohol Withdrawal Delirium; Animals; Benzodiazepines; Brain; Crosses; Ethanol; Flurazepam; GABA Agonists; Genetic; Genotype; Glutamate Decarboxylase; Inbred C57BL; Inbred Strains; Isoxazoles; Knockout; Male; Mice; Motor Skills; Neurologic Mutants; Phenotype; Postural Balance; Species Specificity; Taste

MicroRNAs: master regulators of ethanol abuse and toxicity? - Miranda, Rajesh C.; Pietrzykowski, Andrzej Z.; Tang, Yueming; Sathyan, Pratheesh; Mayfield, Dayne; Keshavarzian, Ali; Sampson, Wayne; Hereld, Dale (Alcoholism, Clinical and Experimental Research, 2010)
Ethanol exerts complex effects on human physiology and health. Ethanol is not only addictive, but it is also a fetal teratogen, an adult neurotoxin, and an etiologic agent in hepatic and cardiovascular disease, inflammation, bone loss, and fracture susceptibility. A large number of genes and signaling mechanisms have been implicated in ethanol's deleterious effects leading to the suggestion that ethanol is a "dirty drug." An important question is, are there cellular "master-switches" that can explain these pleiotropic effects of ethanol? MicroRNAs (miRNAs) have been recently identified as master regulators of the cellular transcriptome and proteome. miRNAs play an increasingly appreciated and crucial role in shaping the differentiation and function of tissues and organs in both health and disease. This critical review discusses new evidence showing that ethanol-sensitive miRNAs are indeed regulatory master-switches. More specifically, miRNAs control the development of tolerance, a crucial component of ethanol addiction. Other drugs of abuse also target some ethanol-sensitive miRNAs suggesting that common biochemical mechanisms underlie addiction. This review also discusses evidence that miRNAs mediate several ethanol pathologies, including disruption of neural stem cell proliferation and differentiation in the exposed fetus, gut leakiness that contributes to endotoxemia and alcoholic liver disease, and possibly also hepatocellular carcinomas and other gastrointestinal cancers. Finally, this review provides a perspective on emerging investigations into potential roles of miRNAs as mediators of ethanol's effects on inflammation and fracture healing, as well as the potential for miRNAs as diagnostic biomarkers and as targets for therapeutic interventions for alcohol-related disorders.
Keywords: alcoholism; Animals; Cell Death; Ethanol; Humans; MicroRNAs; Signal Transduction

Postnatal developmental profile of urocortin 1 and cocaine- and amphetamine-regulated transcript in the perioculomotor region of C57BL/6J mice - Cservenka, Anita; Spangler, Erika; Cote, Dawn M.; Ryabinin, Andrey E. (Brain Research, 2010)
Urocortin 1 (Ucn 1) is an endogenous corticotropin releasing factor (CRF)-related peptide. Ucn 1 is most highly expressed in the perioculomotor urocortin containing neurons (pIIIu), previously known as the non-preganglionic Edinger-Westphal nucleus (npEW). Various studies indicate that these cells are involved in stress adaptation and the regulation of ethanol (EtOH) intake. However, the developmental trajectory of these neurons remained unexamined. Expression of the cocaine- and amphetamine-regulated transcript (CART), which co-localizes with Ucn 1 in the perioculomotor area (pIII) has been examined prenatally, but not postnatally. The goal of the current study was to characterize the ontogenetic profile of Ucn 1 and CART during postnatal development in C57BL/6J (B6) mice. B6 mice were bred, and brains were collected at postnatal days (PND) 1, 4, 8, 12, 16, 24 and 45. Brightfield immunohistochemical staining for Ucn 1 and CART showed that Ucn 1-immunoreactivity (ir) was absent at PND 1, while CART-ir was already apparent in pIIIu at birth, a finding indicating that although the pIIIu neurons have already migrated to their adult position, Ucn 1 expression is triggered in them at later postnatal stages. Ucn 1-ir gradually increased with age, approaching adult levels at PND 16. This developmental profile was confirmed by double-immunofluorescence, which showed that Ucn 1 was absent in CART-positive cells of pIII at PND 4 and that Ucn 1 and CART are strongly but not completely co-localized in pIII at PND 24. Quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) analysis confirmed that Ucn 1 mRNA levels are significantly lower at PND 4 and PND 12 than in adult animals. The lack of brain Ucn 1 immunoreactivity at birth and the gradual postnatal increase in Ucn 1 in pIIIu suggests that this peptide plays a greater behavioral role in adulthood than during the early postnatal development of an organism.
Keywords: Animals; Brain; Developmental; Fluorescent Antibody Technique; Gene Expression Regulation; Immunohistochemistry; Inbred C57BL; Male; Messenger; Mice; Nerve Tissue Proteins; Neurons; Newborn; Reverse Transcriptase Polymerase Chain Reaction; RNA; Urocortins

A potential role for adiponectin receptor 2 (AdipoR2) in the regulation of alcohol intake - Repunte-Canonigo, Vez; Berton, Fulvia; Cottone, Pietro; Reifel-Miller, Anne; Roberts, Amanda J.; Morales, Marisela; Francesconi, Walter; Sanna, Pietro Paolo (Brain research, 2010)
The anterior cingulate cortex (ACC) has been implicated in alcohol and drug addiction. We recently identified the small G protein K-ras as an alcohol-regulated gene in the ACC by gene expression analysis. We show here that the adiponectin receptor 2 (AdipoR2) was differentially regulated by alcohol in the ACC in a K-ras-dependent manner. Additionally, withdrawal-associated increased drinking was attenuated in AdipoR2 null mice. Intracellular recordings revealed that adiponectin increased the excitability of ACC neurons and that this effect was more pronounced during alcohol withdrawal, suggesting that AdipoR2 signaling may contribute to increased ACC activity. Altogether, the data implicate K-ras-regulated pathways involving AdipoR2 in the cellular and behavioral actions of alcohol that may contribute to overactivity of the ACC during withdrawal and excessive alcohol drinking.

Proteomic insights into an expanded cellular role for cytoplasmic lipid droplets - Hodges, Brittany D. M.; Wu, Christine C. (Journal of Lipid Research, 2010)
Cytoplasmic lipid droplets (CLDs) are cellular structures composed of a neutral lipid core surrounded by a phospholipid monolayer of amphipathic lipids and a variety of proteins. CLDs have classically been regarded as cellular energy storage structures. However, recent proteomic studies reveal that, although many of the proteins found to associate with CLDs are connected to lipid metabolism, storage, and homeostasis, there are also proteins with no obvious connection to the classical function and typically associated with other cellular compartments. Such proteins are termed refugee proteins, and their presence suggests that CLDs may serve an expanded role as a dynamic protein storage site, providing a novel mechanism for the regulation of protein function and transport.
Keywords: Animals; Cytoplasm; Humans; Lipid Metabolism; Lipids; Proteomics

Quantitative improvements in peptide recovery at elevated chromatographic temperatures from μLC/MS analyses of brain using SRM mass spectrometry - Farias, Santiago E.; Kline, Kelli G.; Klepacki, Jacek; Wu, Christine C. (Analytical chemistry, 2010)
Elevated chromatographic temperatures are well recognized to provide beneficial analytical effects. Previously, we demonstrated that elevated chromatographic temperature enhances the identification of hydrophobic peptides prepared from enriched membrane samples. Here, we quantitatively assess and compare the recovery of peptide analytes from both simple and complex tryptic peptide matrices using the SRM mass spectrometry. Our study demonstrates that elevated chromatographic temperature results in significant improvements in the magnitude of peptide recovery for both hydrophilic and hydrophobic peptides from both simple and complex peptide matrices. Importantly, the analytical benefits for quantitative measurements in whole mouse brain matrix are demonstrated, suggesting broad utility in the proteomic analyses of complex mammalian tissues. Any improvement in peptide recovery from chromatographic separations translates directly to the apparent sensitivity of downstream mass analysis in μLC-MS/MS based proteomic applications. Therefore, the incorporation of elevated chromatographic temperatures should result in significant improvements in peptide quantification as well as detection and identification.

Reward sensitivity: issues of measurement, and achieving consilience between human and animal phenotypes - Stephens, David N.; Duka, Theodora; Crombag, Hans S.; Cunningham, Christopher L.; Heilig, Markus; Crabbe, John C. (Addiction Biology, 2010)
Reward is a concept fundamental to discussions of drug abuse and addiction. The idea that altered sensitivity to either drug-reward, or to rewards in general, contributes to, or results from, drug-taking is a common theme in several theories of addiction. However, the concept of reward is problematic in that it is used to refer to apparently different behavioural phenomena, and even to diverse neurobiological processes (reward pathways). Whether these different phenomena are different behavioural expressions of a common underlying process is not established, and much research suggests that there may be only loose relationships among different aspects of reward. Measures of rewarding effects of drugs in humans often depend upon subjective reports. In animal studies, such insights are not available, and behavioural measures must be relied upon to infer rewarding effects of drugs or other events. In such animal studies, but also in many human methods established to objectify measures of reward, many other factors contribute to the behaviour being studied. For that reason, studying the biological (including genetic) bases of performance of tasks that ostensibly measure reward cannot provide unequivocal answers. The current overview outlines the strengths and weaknesses of current approaches that hinder the conciliation of cross-species studies of the genetics of reward sensitivity and the dysregulation of reward processes by drugs of abuse. Some suggestions are made as to how human and animal studies may be made to address more closely homologous behaviours, even if those processes are only partly able to isolate 'reward' from other factors contributing to behavioural output.
Keywords: and Conduct Disorders; Animals; Brain; Cerebrovascular Circulation; Choice Behavior; Cocaine-Related Disorders; Conditioning (Psychology); Disruptive; Habituation; Humans; Impulse Control; Phenotype; Psychological Theory; Psychophysiologic; Reward; Sensitivity and Specificity

Superadditive effects of ethanol and flunitrazepam: implications of using immunopharmacotherapy as a therapeutic - Treweek, Jennifer B.; Roberts, Amanda J.; Janda, Kim D. (Molecular Pharmaceutics, 2010)
While benzodiazepine intoxication alone may elicit sedative and antianxiety effects, alcohol coingestion greatly amplifies this central nervous system depression. As a result, this drug combination gained notoriety for its role in cases of facilitated sexual assault and fatal overdose. We previously validated the ability of the novel antiflunitrazepam monoclonal antibody (mAb) RCA3A3 to bind flunitrazepam (FLU) in vivo and block FLU-induced impairment of locomotion and memory. A therapeutically relevant application of this high affinity mAb (K(d,app) = 200 nM), however, is to the more tenuous indication of flunitrazepam (FLU) and alcohol cointoxication. Employing a murine behavioral model, passive immunization with mAb RCA3A3 before injection of ethanol (EtOH: low-dose, 1 g/kg, or high-dose, 1.5 g/kg), FLU (0.06 mg/kg), or a cocktail of both drugs offered partial to full restoration of motor activity levels in co-drug treated and FLU-treated mouse groups (n = 12), respectively. Whereas all drug treatments left contextual learning intact, auditory cued learning was severely disrupted. Prophylactic administration of mAb RCA3A3 prevented this deficit in cued learning in FLU-treated mice but not in the FLU- and EtOH-treated mice, in which co-drug exposure exacerbated the impairment in cued fear conditioning. To substantiate this finding, a dose-response study was performed, and the changes in locomotor activity incurred by different FLU (low-dose, 0.06 mg/kg, or high-dose, 0.09 mg/kg), EtOH (1.0 g/kg, 1.5 g/kg), and mAb RCA3A3 (14.5 mg/kg, 21.8 mg/kg) dose combinations illustrated the potentiation in motor effects by concomitant exposure to FLU and EtOH. Thus, motor activity and fear conditioning results demonstrated that both the amount of FLU left unbound by antibody and the pharmacological additivity between FLU and EtOH, a GABA mimetic, were limiting factors in the therapeutic efficacy of mAb RCA3A3. In sum, our study highlights the complex nature of psychomotor impairment upon co-drug versus singular drug exposure, which may pose a unique challenge to therapeutic treatment.
Keywords: Animal; Animals; Antibodies; Disease Models; Dose-Response Relationship; Drug; Ethanol; Female; Flunitrazepam; Immunotherapy; Injections; Intraperitoneal; Mice; Monoclonal; Psychomotor Performance

T2 relaxation times of 13C metabolites in a rat hepatocellular carcinoma model measured in vivo using 13C-MRS of hyperpolarized [1-13C]pyruvate - Yen, Yi-Fen; Le Roux, Patrick; Mayer, Dirk; King, Randy; Spielman, Daniel; Tropp, James; Pauly, Kim Butts; Pfefferbaum, Adolf; Vasanawala, Shreyas; Hurd, Ralph (NMR in biomedicine, 2010)
A single-voxel Carr-Purcell-Meibloom-Gill sequence was developed to measure localized T2 relaxation times of 13C-labeled metabolites in vivo for the first time. Following hyperpolarized [1-13C]pyruvate injections, pyruvate and its metabolic products, alanine and lactate, were observed in the liver of five rats with hepatocellular carcinoma and five healthy control rats. The T2 relaxation times of alanine and lactate were both significantly longer in HCC tumors than in normal livers (p < 0.002). The HCC tumors also showed significantly higher alanine signal relative to the total 13C signal than normal livers (p < 0.006). The intra- and inter-subject variations of the alanine T2 relaxation time were 11% and 13%, respectively. The intra- and inter-subject variations of the lactate T2 relaxation time were 6% and 7%, respectively. The intra-subject variability of alanine to total carbon ratio was 16% and the inter-subject variability 28%. The intra-subject variability of lactate to total carbon ratio was 14% and the inter-subject variability 20%. The study results show that the signal level and relaxivity of [1-13C]alanine may be promising biomarkers for HCC tumors. Its diagnostic values in HCC staging and treatment monitoring are yet to be explored.

Type 7 adenylyl cyclase-mediated hypothalamic-pituitary-adrenal axis responsiveness: influence of ethanol and sex - Pronko, Sergey P.; Saba, Laura M.; Hoffman, Paula L.; Tabakoff, Boris (The Journal of Pharmacology and Experimental Therapeutics, 2010)
Although ethanol has been considered to be an anxiolytic agent, consumption of ethanol has also been shown to increase plasma adrenocorticotropin and glucocorticoids. The corticotrophin-releasing factor (CRF) receptor 1alpha (CRF-R1) is a G protein-coupled receptor that activates adenylyl cyclase (AC), leading to adrenocorticotropin (and subsequently glucocorticoid) release into the circulation. There are nine members of the membrane-bound AC family, and the type 7 AC (AC7) is most sensitive to ethanol, which enhances the responsiveness of AC7 to G protein-coupled receptor activation. We determined the time course of ethanol's effect on plasma adrenocorticotropin and corticosterone levels in male and female AC7 transgenic (Adcy7(huTG)) mice (in which AC7 is overexpressed in neural tissue) and AC7 heterozygous knockdown [Adcy7(+/-)] mice (in which AC7 is underexpressed in neural tissue), and their respective littermate controls [wild type (WT)]. CRF-R1 mRNA and mRNA and protein for different forms of ACs were measured by using gene expression arrays, quantitative reverse transcription-polymerase chain reaction, and immunoblotting in pituitaries of all animals. Our results demonstrated increased levels of AC7 in pituitary of Adcy7(huTG) mice and decreased levels in pituitary of Adcy7(+/-) mice compared with WT animals. Male and female Adcy7(huTG) mice displayed higher plasma adrenocorticotropin and corticosterone levels than WT and/or Adcy7(+/-) mice after ethanol injection. Female mice displayed higher adrenocorticotropin and corticosterone levels after ethanol injection than males, regardless of genotype. The data provide evidence for an integral role of AC7 in the increase of plasma adrenocorticotropin and corticosterone levels during alcohol intoxication.
Keywords: Adenylyl Cyclases; Adrenocorticotropic Hormone; Animals; Central Nervous System Depressants; Corticosterone; Ethanol; Female; Humans; Hypothalamo-Hypophyseal System; Immunoblotting; Knockout; Male; Mice; Pituitary-Adrenal System; Reverse Transcriptase Polymerase Chain Reaction; Sex Characteristics; Transgenic

Withdrawal severity after chronic intermittent ethanol in inbred mouse strains - Metten, Pamela; Sorensen, Michelle L.; Cameron, Andy J.; Yu, Chia-Hua; Crabbe, John C. (Alcoholism, Clinical and Experimental Research, 2010)
BACKGROUND: To study withdrawal, ethanol is usually administered chronically without interruption. However, interest has recurred in models of episodic exposure. Increasing evidence suggests that chronic intermittent exposure to ethanol leads to a sensitization effect in both withdrawal severity and ethanol consumption. The goal of the present study was to examine mouse inbred strain differences in withdrawal severity following chronic intermittent exposure using the handling-induced convulsion as the behavioral endpoint. We also sought to compare the withdrawal responses of inbred strains across acute, chronic continuous, and chronic intermittent exposure regimens. METHODS: Male mice from 15 standard inbred strains were exposed to ethanol vapor for 16 hours each day for 3 days and removed to an air chamber during the intervening 8 hours. Mice in the control groups were handled the same, except that they were exposed only to air. Daily blood ethanol concentrations were averaged for each mouse to estimate total dose of ethanol experienced. RESULTS: Across strains, mice had an average daily blood ethanol concentration (BEC) of 1.45 +/- 0.02 mg/ml and we restricted the range of this value to 1.00-2.00 mg/ml. To evaluate strain differences, we divided data into two dose groups based on BEC, low dose (1.29 +/- 0.1 mg/ml) and high dose (1.71 +/- 0.02 mg/ml). After the third inhalation exposure, ethanol-exposed and air-exposed groups were tested hourly for handling-induced convulsions for 10 hour and at hour 24 and 25. Strains differed markedly in the severity of withdrawal (after subtraction of air control values) in both dose groups. CONCLUSION: The chronic intermittent exposure paradigm is sufficient to elicit differential withdrawal responses across nearly all strains. Data from the high-dose groups correlated well with withdrawal data derived from prior acute (single high dose) and chronic continuous (for 72 hours) ethanol withdrawal studies, supporting the influence of common genes on all three responses.
Keywords: Alcohol Withdrawal Seizures; Animals; Dose-Response Relationship; Drug; Ethanol; Inbred Strains; Male; Mice; Species Specificity

Agonism of the endocannabinoid system modulates binge-like alcohol intake in male C57BL/6J mice: involvement of the posterior ventral tegmental area - Linsenbardt, D. N.; Boehm, S. L. (Neuroscience, 2009)
Recent studies have indicated a role for the endocannabinoid system in the behavioral and physiological effects of alcohol (ethanol), particularly ethanol seeking behaviors. However, its role in modulating binge-like intake and/or the mechanism by which it may exert these effects remain poorly understood. The current study used a newly developed strain-specific animal model of binge drinking, dubbed 'Drinking In the Dark' (DID), to determine if facilitation of the endocannabinoid system with the synthetic cannabinoid agonist WIN 55-212,2 (WIN) modulates binge-like ethanol intake in male C57BL/6J (B6) mice. Based on the results of these systemic (i.p.) manipulations, and evidence in support of the involvement of subregions of the Ventral Tegmental Area (VTA) in governing self-administration of ethanol (Rodd-Henricks et al., (2000) Psychopharmacology (Berl) 149(3):217-224) as well as binge-like intake using the DID model (Moore & Boehm, (2009 Behav Neurosci 123(3):555-563), we extended these findings to evaluate the role of the endocannabinoid system within the anterior and posterior sub regions of the VTA using site-specific microinjections. Consistent with previous research, the lowest systemic dose of WIN (0.5 mg/kg) significantly increased ethanol intake in the first 30 minutes of access whereas the two highest doses (1 and 2 mg/kg) decreased ethanol intake within this time interval. Intra-posterior ventral tegmental area (pVTA) (but not aVTA (anterior ventral tegmental area) microinjections elicited time-dependent and dose-dependent increases (0.25 and 0.5 mug/side) and decreases (2.5 mug/side) in ethanol intake. Importantly, follow-up studies revealed that in some cases alterations in fluid consumption may have been influenced by competing locomotor activity (or inactivity). The present data are consistent with previous research in that agonism of the endocannabinoid system increases ethanol intake in rodents and implicate the pVTA in the modulation of drinking to intoxication. Moreover, the dose-dependent alterations in locomotor activity emphasize the importance of directly assessing multiple (possibly competing) behaviors when evaluating drug effects on voluntary consumption.
Keywords: Alcohol Drinking; Animals; Benzoxazines; Cannabinoid Receptor Modulators; Dose-Response Relationship; Drug; Endocannabinoids; Ethanol; Follow-Up Studies; Inbred C57BL; Locomotion; Male; Mice; Microinjections; Morpholines; Naphthalenes; Self Administration; Time Factors; Ventral tegmental area

Application of subsecond spiral chemical shift imaging to real-time multislice metabolic imaging of the rat in vivo after injection of hyperpolarized 13C1-pyruvate - Mayer, Dirk; Yen, Yi-Fen; Tropp, James; Pfefferbaum, Adolf; Hurd, Ralph E.; Spielman, Daniel M. (Magnetic Resonance in Medicine, 2009)
Dynamic nuclear polarization can create hyperpolarized compounds with MR signal-to-noise ratio enhancements on the order of 10,000-fold. Both exogenous and normally occurring endogenous compounds can be polarized, and their initial concentration and downstream metabolic products can be assessed using MR spectroscopy. Given the transient nature of the hyperpolarized signal enhancement, fast imaging techniques are a critical requirement for real-time metabolic imaging. We report on the development of an ultrafast, multislice, spiral chemical shift imaging sequence, with subsecond acquisition time, achieved on a clinical MR scanner. The technique was used for dynamic metabolic imaging in rats, with measurement of time-resolved spatial distributions of hyperpolarized (13)C(1)-pyruvate and metabolic products (13)C(1)-lactate and (13)C(1)-alanine, with a temporal resolution of as fast as 1 s. Metabolic imaging revealed different signal time courses in liver from kidney. These results demonstrate the feasibility of real-time, hyperpolarized metabolic imaging and highlight its potential in assessing organ-specific kinetic parameters.
Keywords: Algorithms; Animals; Brain; Carbon Isotopes; Computer Systems; Injections; Intravenous; Magnetic Resonance Imaging; Magnetic Resonance Spectroscopy; Male; Pyruvic Acid; Rats; Tissue Distribution; Wistar

Circadian timing of ethanol exposure exerts enduring effects on subsequent ad libitum consumption in C57 mice - Trujillo, Jennifer L.; Roberts, Amanda J.; Gorman, Michael R. (Alcoholism, Clinical and Experimental Research, 2009)
BACKGROUND: There is a daily rhythm in the voluntary intake of ethanol in mice, with greatest consumption in the early night and lowest intake during the day. The role of daily timing of ethanol exposure on the development and control of long-term ethanol self-administration has been neglected. The present study examines these issues using C57BL/6J mice. METHODS: Mice were repeatedly exposed to 10% ethanol for 2 hours early in the night or day for several weeks. Subsequently, ethanol was available at the opposite time (Expt 1) or 24 hours daily (Expts 1 and 2). Lick sensors recorded the patterns of drinking activity in Experiment 2. RESULTS: Mice exposed to ethanol during the night drink more than mice exposed during the day. Prior history did not affect ethanol intake when the schedule was reversed. Under 24-hour exposure conditions, mice with a history of drinking during the night consumed significantly more than mice drinking during the day. The circadian patterns of drinking were not altered. CONCLUSIONS: These results demonstrate that the daily timing of ethanol exposure exerts enduring effects of self-administration of ethanol in mice. Understanding how circadian rhythms regulate ethanol consumption may be valuable for modifying subsequent intake.
Keywords: Alcohol Drinking; Animals; Circadian Rhythm; Ethanol; Inbred C57BL; Male; Mice; Motor Activity; Random Allocation

Contribution of early environmental stress to alcoholism vulnerability - Campbell, Joannalee C.; Szumlinski, Karen K.; Kippin, Tod E. (Alcohol (Fayetteville, N.Y.), 2009)
The most problematic aspects of alcohol abuse disorder are excessive alcohol consumption and the inability to refrain from alcohol consumption during attempted abstinence. The root causes that predispose certain individuals to these problems are poorly understood but are believed to be produced by a combination of genetic and environmental factors. Early environmental trauma alters neurodevelopmental trajectories that can predispose an individual to a number of neuropsychiatric disorders, including substance abuse. Prenatal stress (PNS) is a well-established protocol that produces perturbations in nervous system development, resulting in behavioral alterations that include hyperresponsiveness to stress, novelty, and psychomotor stimulant drugs (e.g., cocaine, amphetamine). Moreover, PNS animals exhibit enduring alterations in basal and cocaine-induced changes in dopamine and glutamate transmission within limbic structures, which exhibit pathology in drug addiction and alcoholism, suggesting that these alterations may contribute to an increased propensity to self-administer large amounts of drugs of abuse or to relapse after periods of drug withdrawal. Given that cocaine and alcohol have actions on common limbic neural substrates (albeit by different mechanisms), we hypothesized that PNS would elevate the motivation for, and consumption of, alcohol. Accordingly, we have found that male C57BL/6J mice subject to PNS exhibit higher operant responding and consume more alcohol during alcohol reinforcement as adults. Alterations in glutamate and dopamine neurotransmission within the forebrain structures appear to contribute to the PNS-induced predisposition to high alcohol intake and are induced by excessive alcohol intake. Accordingly, we are exploring the interactions between neurochemical changes produced by PNS and changes induced by consumption of alcohol in adulthood to model the biological bases of high vulnerability to alcohol abuse.
Keywords: alcoholism; Animals; Female; Humans; Male; Mice; Nucleus Accumbens; Physiological; Pregnancy; Prenatal Exposure Delayed Effects; Reward; Stress

Deletion of vanilloid receptor (TRPV1) in mice alters behavioral effects of ethanol - Blednov, Y. A.; Harris, R. A. (Neuropharmacology, 2009)
The vanilloid receptor TRPV1 is activated by ethanol and this may be important for some of the central and peripheral actions of ethanol. To determine if this receptor has a role in ethanol-mediated behaviors, we studied null mutant mice in which the Trpv1 gene was deleted. Mice lacking this gene showed significantly higher preference for ethanol and consumed more ethanol in a two-bottle choice test as compared with wild type littermates. Null mutant mice showed shorter duration of loss of righting reflex induced by low doses of ethanol (3.2 and 3.4 g/kg) and faster recovery from motor incoordination induced by ethanol (2 g/kg). However, there were no differences between null mutant and wild type mice in severity of ethanol-induced acute withdrawal (4 g/kg) or conditioned taste aversion to ethanol (2.5 g/kg). Two behavioral phenotypes (decreased sensitivity to ethanol-induced sedation and faster recovery from ethanol-induced motor incoordination) seen in null mutant mice were reproduced in wild type mice by injection of a TRPV1 antagonist, capsazepine (10 mg/kg). These two ethanol behaviors were changed in the opposite direction after injection of capsaicin, a selective TRPV1 agonist, in wild type mice. The studies provide the first evidence that TRPV1 is important for specific behavioral actions of ethanol.
Keywords: Alcohol Drinking; Animals; Capsaicin; Central Nervous System Depressants; Choice Behavior; Ethanol; Inbred C57BL; Knockout; Mice; Postural Balance; Substance Withdrawal Syndrome; Taste; TRPV Cation Channels

Detection of reciprocal quantitative trait loci for acute ethanol withdrawal and ethanol consumption in heterogeneous stock mice - Hitzemann, R.; Edmunds, S.; Wu, W.; Malmanger, B.; Walter, N.; Belknap, J.; Darakjian, P.; McWeeney, S. (Psychopharmacology, 2009)
RationalePrevious studies have suggested that there is an inverse genetic relationship between ethanol consumption (two-bottle choice, continuous access) and ethanol withdrawal (e.g., Metten et al., Behav Brain Res 95:113–122, 1998a).ObjectivesThe current study used short-term selective breeding from heterogeneous stock (HS) animals to examine this relationship. The primary goal of the current study was to determine if reciprocal quantitative trait loci (QTLs) could be found in the selectively bred lines. The advantage of detecting QTLs in HS animals is that it is possible to extract a haplotype signature for the QTL, which in turn can be used to narrow the number of candidate genes generated from gene expression and sequence databases (see, e.g., Hitzemann et al., Mamm Genome 14:733–747, 2003).ResultsSeven reciprocal QTLs were detected on chromosomes (Chr) 1 (two), 3, 6, 11, 16, and 17 that exceeded the nominal LOD threshold of 10; genetic drift, which occurs during selection, dramatically increases the LOD threshold. The proximal Chr 1 QTL was examined in some detail. The haplotype structure of the QTL was such that the LP/J allele was associated with low withdrawal and high consumption. The QTL appears to be located in a gene-poor region between 170 and 173 Mbp. Based on available sequence data, two plausible candidate genes emerge—Nos1ap and Atf6α.ConclusionsThe data presented here confirm some aspects of the negative genetic relationship between acute ethanol withdrawal and ethanol consumption. The QTL data point to the potential involvement of NO signaling and/or the unfolded protein response.

Differential activation of limbic circuitry associated with chronic ethanol withdrawal in DBA/2J and C57BL/6J mice - Chen, Gang; Reilly, Matthew T.; Kozell, Laura B.; Hitzemann, Robert; Buck, Kari J. (Alcohol (Fayetteville, N.Y.), 2009)
Although no animal model exactly duplicates clinically defined alcoholism, models for specific factors, such as the withdrawal syndrome, are useful for identifying potential neural determinants of liability in humans. The well-documented difference in withdrawal severity following chronic ethanol exposure, between the DBA/2J and C57BL/6J mouse strains, provides an excellent starting point for dissecting the neural circuitry affecting predisposition to physical dependence on ethanol. To induce physical dependence, we used a paradigm in which mice were continuously exposed to ethanol vapor for 72h. Ethanol-exposed and air-exposed (control) mice received daily injections of pyrazole hydrochloride, an alcohol dehydrogenase inhibitor, to stabilize blood ethanol levels. Ethanol-dependent and air-exposed mice were killed 7h after removal from the inhalation chambers. This time point corresponds to the time of peak ethanol withdrawal severity. The brains were processed to assess neural activation associated with ethanol withdrawal indexed by c-Fos immunostaining. Ethanol-withdrawn DBA/2J mice showed significantly (P<.05) greater neural activation than ethanol-withdrawn C57BL/6J mice in the dentate gyrus, hippocampus CA3, lateral septum, basolateral and central nuclei of the amygdala, and prelimbic cortex. Taken together with results using an acute model, our data suggest that progression from acute ethanol withdrawal to the more severe withdrawal associated with physical dependence following chronic ethanol exposure involves recruitment of neurons in the hippocampal formation, amygdala, and prelimbic cortex. To our knowledge, these are the first studies to use c-Fos to identify the brain regions and neurocircuitry that distinguish between chronic and acute ethanol withdrawal severity using informative animal models.
Keywords: alcoholism; Animal; Animals; Cerebral Cortex; Disease Models; Ethanol; Hippocampus; Inbred C57BL; Inbred DBA; limbic system; Male; Mice; Proto-Oncogene Proteins c-fos; Species Specificity; Substance Withdrawal Syndrome

Differential Effects of Chronic Ethanol Consumption and Withdrawal on Homer/Glutamate Receptor Expression in Subregions of the Accumbens and Amygdala of P Rats - Obara, Ilona; Bell, Richard L.; Goulding, Scott P.; Reyes, Cindy M.; Larson, Lindsay A.; Ary, Alexis W.; Truitt, William A.; Szumlinski, Karen K. (Alcoholism, clinical and experimental research, 2009)
Background Homer proteins are constituents of scaffolding complexes that regulate the trafficking and function of central Group1 metabotropic glutamate receptors (mGluRs) and N-methyl-D-aspartate (NMDA) receptors. Research supports the involvement of these proteins in ethanol-induced neuroplasticity in mouse. In this study, we examined the effects of short versus long-term withdrawal from chronic ethanol consumption on Homer and glutamate receptor protein expression within striatal and amygdala subregions of selectively bred, alcohol-preferring P rats. Methods For 6 months, male P rats had concurrent access to 15% and 30% ethanol solutions under intermittent (IA: 4 d/wk) or continuous (CA: 7 d/wk) access conditions in their home cage. Rats were killed 24 hours (short withdrawal: SW) or 4 weeks (long withdrawal: LW) after termination of ethanol access, subregions of interest were micropunched and tissue processed for detection of Group1 mGluRs, NR2 subunits of the NMDA receptor and Homer protein expression. Results Within the nucleus accumbens (NAC), limited changes in NR2a and NR2b expression were detected in the shell (NACsh), whereas substantial changes were observed for Homer2a/b, mGluRs as well as NR2a and NR2b subunits in the core (NACc). Within the amygdala, no changes were detected in the basolateral subregion, whereas substantial changes, many paralleling those observed in the NACc, were detected in the central nucleus (CeA) subregion. In addition, most of the changes observed in the CeA, but not NACc, were present in both SW and LW rats. Conclusions Overall, these subregion specific, ethanol-induced increases in mGluR/Homer2/NR2 expression within the NAC and amygdala suggest changes in glutamatergic plasticity had taken place. This may be a result of learning and subsequent memory formation of ethanol’s rewarding effects in these brain structures, which may, in part, mediate the chronic relapsing nature of alcohol abuse.

Differential effects of ethanol in the nucleus accumbens shell of alcohol-preferring (P), alcohol-non-preferring (NP) and Wistar rats: a proteomics study - McBride, William J.; Schultz, Jonathan A.; Kimpel, Mark W.; McClintick, Jeanette N.; Wang, Mu; You, Jinsam; Rodd, Zachary A. (Pharmacology, Biochemistry, and Behavior, 2009)
The objective of this study was to determine the effects of ethanol injections on protein expression in the nucleus accumbens shell (ACB-sh) of alcohol-preferring (P), alcohol-non-preferring (NP) and Wistar (W) rats. Rats were injected for 5 consecutive days with either saline or 1 g/kg ethanol; 24 h after the last injection, rats were killed and brains obtained. Micro-punch samples of the ACB-sh were homogenized; extracted proteins were subjected to trypsin digestion and analyzed with a liquid chromatography-mass spectrometer procedure. Ethanol changed expression levels (1.15-fold or higher) of 128 proteins in NP rats, 22 proteins in P, and 28 proteins in W rats. Few of the changes observed with ethanol treatment for NP rats were observed for P and W rats. Many of the changes occurred in calcium-calmodulin signaling systems, G-protein signaling systems, synaptic structure and histones. Approximately half the changes observed in the ACB-sh of P rats were also observed for W rats. Overall, the results indicate a unique response to ethanol of the ACB-sh of NP rats compared to P and W rats; this unique response may reflect changes in neuronal function in the ACB-sh that could contribute to the low alcohol drinking behavior of the NP line.
Keywords: Animals; Chromatography; Ethanol; Liquid; Male; Nucleus Accumbens; Proteomics; Rats; Sensitivity and Specificity; Tandem Mass Spectrometry; Wistar

Differential sensitivity of the perioculomotor urocortin-containing neurons to ethanol, psychostimulants and stress in mice and rats - Spangler, E.; Cote, D. M.; Anacker, A. M. J.; Mark, G. P.; Ryabinin, A. E. (Neuroscience, 2009)
The perioculomotor urocortin-containing population of neurons (pIIIu: otherwise known as the non-preganglionic Edinger-Westphal nucleus) is sensitive to alcohol and is involved in the regulation of alcohol intake. A recent study indicated that this brain region is also sensitive to psychostimulants. Since pIIIu has been shown to respond to stress, we investigated how psychostimulant-induced pIIIu activation compares to stress- and ethanol-induced activation, and whether it is independent from a generalized stress response. Several experiments were performed to test how the pIIIu responds to psychostimulants by quantifying the number of Fos immunoreactive nuclei after acute i.p. injections of saline, 10-30 mg/kg cocaine, 5 mg/kg methamphetamine, 5 mg/kg amphetamine, 2.5 g/kg ethanol, 2 h of restraint stress, 10 min of swim stress, or six applications of mild foot shock in male C57BL/6 J mice. We also compared Fos immunoreactivity in pIIIu after acute (20 mg/kg cocaine) and repeated cocaine exposure (7 days of 20 mg/kg cocaine) injections in male C57BL/6 J mice in order to investigate the potential habituation of this response. Finally, we quantified the number of Fos immunoreactive nuclei in pIIIu after administration of saline, 2.5 g/kg ethanol, 20 mg/kg cocaine, or 2 h of restraint stress in male Sprague-Dawley rats. We found that exposure to psychostimulants and ethanol induced significantly higher Fos levels in pIIIu compared to stress in mice. Furthermore, repeated cocaine injections did not decrease Fos immunoreactivity as would be expected if this response were due to stress. In rats, exposure to ethanol, psychostimulant and restraint stress all induced pIIIu Fos immunoreactivity compared to saline-injected controls. In both mice and rats, ethanol- and cocaine-induced Fos immunoreactivity occurred exclusively in urocortin 1-positive, but not in tyrosine hydroxylase-positive, cells. These results provide evidence that the pIIIu Fos-response to psychostimulants is independent of a generalized stress in mice, but not rats. They additionally show that the pIIIu response to stress differs significantly between species.
Keywords: Amphetamine; Animals; Central Nervous System Depressants; Central Nervous System Stimulants; Cocaine; Ethanol; Inbred C57BL; Male; Mesencephalon; Methamphetamine; Mice; Neurons; Proto-Oncogene Proteins c-fos; Psychological; Psychotropic Drugs; Rats; Species Specificity; Sprague-Dawley; Stress; Tyrosine 3-Monooxygenase; Urocortins

Effects of concurrent access to multiple ethanol concentrations and repeated deprivations on alcohol intake of high-alcohol-drinking (HAD) rats - Rodd, Zachary A.; Bell, Richard L.; Kuc, Kelly A.; Murphy, James M.; Lumeng, Lawrence; McBride, William J. (Addiction Biology, 2009)
High-alcohol-drinking rats, given access to 10% ethanol, expressed an alcohol deprivation effect (ADE) only after multiple deprivations. In alcohol-preferring (P) rats, concurrent access to multiple ethanol concentrations combined with repeated cycles of EtOH access and deprivation produced excessive ethanol drinking. The current study was undertaken to examine the effects of repeated alcohol deprivations with concurrent access to multiple concentrations of ethanol on ethanol intake of HAD replicate lines of rats. HAD-1 and HAD-2 rats received access to 10, 20 and 30% (v/v) ethanol for 6 weeks. Rats from each replicate line were assigned to: (1) a non-deprived group; (2) a group initially deprived of ethanol for 2 weeks; or (3) a group initially deprived for 8 weeks. Following the restoration of the ethanol solutions, cycle of 2 weeks of ethanol exposure and 2 weeks of alcohol deprivation was repeated three times for a total of four deprivations. Following the initial ethanol deprivation period, deprived groups significantly increased ethanol intakes during the initial 24-hour re-exposure period. Multiple deprivations increased ethanol intakes, shifted preference to higher ethanol concentrations and prolonged the duration of the elevated ethanol intakes for up to 5 days. In addition, repeated deprivations increased ethanol intake in the first 2-hour re-exposure period as high as 5-7 g/kg (which are equivalent to amounts consumed in 24 hours by HAD rats), and produced blood ethanol levels in excess of 150 mg%. The results indicate that HAD rats exhibit 'loss-of-control' of alcohol drinking with repeated deprivations when multiple ethanol concentrations are available.
Keywords: alcoholism; Animal; Animals; Behavior; Choice Behavior; Disease Models; Ethanol; Food Deprivation; Male; Rats

Electrolytic lesions of the medial nucleus accumbens shell selectively decrease ethanol consumption without altering preference in a limited access procedure in C57BL/6J mice - Dhaher, Ronnie; Finn, Deborah A.; Oberbeck, Denesa L.; Yoneyama, Naomi; Snelling, Christopher C.; Wu, Weiran; Hitzemann, Robert J. (Pharmacology Biochemistry and Behavior, 2009)
The central extended amygdala (cExtA) is a limbic region proposed to play a key role in drug and alcohol addiction and to contain the medial nucleus accumbens shell (MNAc shell). The aim of this study was to examine the involvement of the MNAc shell in ethanol and sucrose consumption in a limited and free access procedure in the C57BL/6J (B6) mouse. Separate groups of mice received bilateral electrolytic lesions of the MNAc shell or sham surgery, and following recovery from surgery, were allowed to voluntarily consume ethanol (15% v/v) in a 2 h limited access 2-bottle-choice procedure. Following 1 week of limited access ethanol consumption, mice were given 1 week of limited access sucrose consumption. A separate group of lesioned and sham mice were given free access (24 h) to ethanol in a 2-bottle choice procedure and were run in parallel to the mice receiving limited access consumption. Electrolytic lesions of the MNAc shell decreased ethanol (but not sucrose) consumption in a limited access procedure, but did not alter free access ethanol consumption. These results suggest that the MNAc shell is a component of the underlying neural circuitry contributing to limited access alcohol consumption in the B6 mouse.
Keywords: C57BL/6J; Electrolytic lesions; Ethanol consumption; Extended amygdala; Nucleus Accumbens; Sucrose consumption

Gene expression changes in the nucleus accumbens of alcohol-preferring rats following chronic ethanol consumption - Bell, Richard L.; Kimpel, Mark W.; McClintick, Jeanette N.; Strother, Wendy N.; Carr, Lucinda G.; Liang, Tiebing; Rodd, Zachary A.; Mayfield, R. Dayne; Edenberg, Howard J.; McBride, William J. (Pharmacology, biochemistry, and behavior, 2009)
The objective of this study was to determine the effects of binge-like alcohol drinking on gene expression changes in the nucleus accumbens (ACB) of alcohol-preferring (P) rats. Adult male P rats were given ethanol under multiple scheduled access (MSA; three 1-hr dark-cycle sessions/day) conditions for 8 weeks. For comparison purposes, a second ethanol drinking group was given continuous/daily alcohol access (CA; 24 hr/day). A third group was ethanol-naïve (W group). Average ethanol intakes for the CA and MSA groups were approximately 9.5 and 6.5 g/kg/day, respectively. Fifteen hr after the last drinking episode, rats were euthanized, the brains extracted, and the ACB dissected. RNA was extracted and purified for microarray analysis. The only significant differences were between the CA and W groups (p < 0.01; Storey false discovery rate = 0.15); there were 374 differences in named genes between these 2 groups. There were 20 significant Gene Ontology (GO) categories, which included negative regulation of protein kinase activity, anti-apoptosis, and regulation of G-protein-coupled receptor signaling. Ingenuity® analysis indicated a network of transcription factors, involving oncogenes (Fos, Jun, Junb had higher expression in the ACB of the CA group), suggesting increased neuronal activity. There were 43 genes located within rat QTLs for alcohol consumption and preference; 4 of these genes (Tgfa, Hspa5, Mtus1 and Creb3l2) are involved in anti-apoptosis and increased transcription, suggesting that they may be contributing to cellular protection and maintaining high alcohol intakes. Overall, these findings suggest that chronic CA drinking results in genomic changes that can be observed during the early acute phase of ethanol withdrawal. Conversely, chronic MSA drinking, with its associated protracted withdrawal periods, results in genomic changes that may be masked by tight regulation of these genes following repeated experiences of ethanol withdrawal.

Gene expression profiling in blood: new diagnostics in alcoholism and addiction? - Mayfield, R Dayne; Harris, R Adron (Neuropsychopharmacology : official publication of the American College of Neuropsychopharmacology, 2009)

Genetical genomic determinants of alcohol consumption in rats and humans - Tabakoff, Boris; Saba, Laura; Printz, Morton; Flodman, Pam; Hodgkinson, Colin; Goldman, David; Koob, George; Richardson, Heather N.; Kechris, Katerina; Bell, Richard L.; Hübner, Norbert; Heinig, Matthias; et al. (BMC Biology, 2009)
We have used a genetical genomic approach, in conjunction with phenotypic analysis of alcohol consumption, to identify candidate genes that predispose to varying levels of alcohol intake by HXB/BXH recombinant inbred rat strains. In addition, in two populations of humans, we assessed genetic polymorphisms associated with alcohol consumption using a custom genotyping array for 1,350 single nucleotide polymorphisms (SNPs). Our goal was to ascertain whether our approach, which relies on statistical and informatics techniques, and non-human animal models of alcohol drinking behavior, could inform interpretation of genetic association studies with human populations.

High throughput sequencing in mice: a platform comparison identifies a preponderance of cryptic SNPs - Walter, Nicole A. R.; Bottomly, Daniel; Laderas, Ted; Mooney, Michael A.; Darakjian, Priscila; Searles, Robert P.; Harrington, Christina A.; McWeeney, Shannon K.; Hitzemann, Robert; Buck, Kari J. (BMC genomics, 2009)
BACKGROUND: Allelic variation is the cornerstone of genetically determined differences in gene expression, gene product structure, physiology, and behavior. However, allelic variation, particularly cryptic (unknown or not annotated) variation, is problematic for follow up analyses. Polymorphisms result in a high incidence of false positive and false negative results in hybridization based analyses and hinder the identification of the true variation underlying genetically determined differences in physiology and behavior. Given the proliferation of mouse genetic models (e.g., knockout models, selectively bred lines, heterogeneous stocks derived from standard inbred strains and wild mice) and the wealth of gene expression microarray and phenotypic studies using genetic models, the impact of naturally-occurring polymorphisms on these data is critical. With the advent of next-generation, high-throughput sequencing, we are now in a position to determine to what extent polymorphisms are currently cryptic in such models and their impact on downstream analyses. RESULTS: We sequenced the two most commonly used inbred mouse strains, DBA/2J and C57BL/6J, across a region of chromosome 1 (171.6 - 174.6 megabases) using two next generation high-throughput sequencing platforms: Applied Biosystems (SOLiD) and Illumina (Genome Analyzer). Using the same templates on both platforms, we compared realignments and single nucleotide polymorphism (SNP) detection with an 80 fold average read depth across platforms and samples. While public datasets currently annotate 4,527 SNPs between the two strains in this interval, thorough high-throughput sequencing identified a total of 11,824 SNPs in the interval, including 7,663 new SNPs. Furthermore, we confirmed 40 missense SNPs and discovered 36 new missense SNPs. CONCLUSION: Comparisons utilizing even two of the best characterized mouse genetic models, DBA/2J and C57BL/6J, indicate that more than half of naturally-occurring SNPs remain cryptic. The magnitude of this problem is compounded when using more divergent or poorly annotated genetic models. This warrants full genomic sequencing of the mouse strains used as genetic models.
Keywords: Animals; Artificial; Bacterial; Chromosomes; DNA; Gene Expression Profiling; Genome; Genomics; Inbred C57BL; Inbred DBA; Mice; Polymorphism; Sequence Alignment; Sequence Analysis; Single Nucleotide

In Vivo Evidence for Alcohol-Induced Neurochemical Changes in Rat Brain Without Protracted Withdrawal, Pronounced Thiamine Deficiency, or Severe Liver Damage - Zahr, Natalie M; Mayer, Dirk; Vinco, Shara; Orduna, Juan; Luong, Richard; Sullivan, Edith V; Pfefferbaum, Adolf (Neuropsychopharmacology : official publication of the American College of Neuropsychopharmacology, 2009)
Magnetic resonance spectroscopy (MRS) studies in human alcoholics report decreases in N-acetylaspartate (NAA) and choline-containing (Cho) compounds. Whether alterations in brain metabolite levels are attributable to alcohol per se or to physiological effects of protracted withdrawal or impaired nutritional or liver status remains unclear. Longitudinal effects of alcohol on brain metabolites measured in basal ganglia with single-voxel MRS were investigated in sibling pairs of wild-type Wistar rats, with one rat per pair exposed to escalating doses of vaporized alcohol, the other to vapor chamber air. MRS was conducted before alcohol exposure and twice during exposure. After 16 weeks of alcohol exposure, rats achieved average blood alcohol levels (BALs) of ~ 293 mg per 100 ml and had higher Cho and a trend for higher glutamine + glutamate (Glx) than controls. After 24 weeks of alcohol exposure, BALs rose to ~ 445 mg per 100 ml, and alcohol-exposed rats had higher Cho, Glx, and glutamate than controls. Thiamine and thiamine monophosphate levels were significantly lower in the alcohol than the control group but did not reach levels low enough to be considered clinically relevant. Histologically, livers of alcohol-exposed rats exhibited greater steatosis and lower glycogenosis than controls, but were not cirrhotic. This study demonstrates a specific pattern of neurobiochemical changes suggesting excessive membrane turnover or inflammation, indicated by high Cho, and alterations to glutamate homeostasis in the rat brain in response to extended vaporized alcohol exposure. Thus, we provide novel in vivo evidence for alcohol exposure as causing changes in brain chemistry in the absence of protracted withdrawal, pronounced thiamine deficiency, or severe liver damage.

In vivo glutamate decline associated with kainic acid-induced status epilepticus - Zahr, Natalie M.; Crawford, Elena L. Fasano; Hsu, Oliver; Vinco, Shara; Mayer, Dirk; Rohlfing, Torsten; Sullivan, Edith V.; Pfefferbaum, Adolf (Brain Research, 2009)
Neurophysiological, biochemical, and anatomical evidence implicates glutamatergic mechanisms in epileptic seizures. Until recently, however, longitudinal characterization of in vivo glutamate dynamics was not possible. Here, we present data using in vivo magnetic resonance spectroscopy (MRS) optimized for the detection of glutamate to identify changes that evolve following kainic acid (KA)-induced status epilepticus. Wild-type male Wistar rats underwent whole-brain MR imaging and single-voxel MRS on a clinical 3 T scanner equipped with a high-strength insert gradient coil. Scanning took place before and then 3 days, 28–32 days, and 42–50 days after induction of status epilepticus. Analyses compared 5 seizure (Sz), 5 no-seizure (NoSz; received KA but did not exhibit seizures), and 6 control (Con) animals. This longitudinal study demonstrated reduced glutamate levels in vivo in the dorsal hippocampus 3 days and 1 month following status epilepticus in Sz animals compared with Con animals. Additionally, previous results were replicated: in the Sz group, computed T2 was higher in the ventral hippocampus and limbic cortex 3 days after seizure activity compared with baseline but resolved in both regions at the 1 month scan, suggesting a transient edema. Three days following seizure activity, N-acetylaspartate (NAA) declined and lactate increased in the dorsal hippocampus of the Sz group compared with the Con and NoSz group; both metabolites approached baseline levels by the third scan. Taken together, these results support the conclusion that seizure activity following KA infusion causes loss of glutamatergic neurons.
Keywords: Cerebellum; glutamate; Hippocampus; Longitudinal; rat; Status epilepticus

In vivo measurement of ethanol metabolism in the rat liver using magnetic resonance spectroscopy of hyperpolarized [1-13C]pyruvate - Spielman, Daniel M.; Mayer, Dirk; Yen, Yi-Fen; Tropp, James; Hurd, Ralph E.; Pfefferbaum, Adolf (Magnetic Resonance in Medicine, 2009)
[1-(13)C]pyruvate is a readily polarizable substrate that has been the subject of numerous magnetic resonance spectroscopy (MRS) studies of in vivo metabolism. In this work (13)C-MRS of hyperpolarized [1-(13)C]pyruvate was used to interrogate a metabolic pathway involved in neither aerobic nor anaerobic metabolism. In particular, ethanol consumption leads to altered liver metabolism, which when excessive is associated with adverse medical conditions including fatty liver disease, hepatitis, cirrhosis, and cancer. Here we present a method for noninvasively monitoring this important process in vivo. Following the bolus injection of hyperpolarized [1-(13)C]pyruvate, we demonstrate a significantly increased rat liver lactate production rate with the coadministration of ethanol (P = 0.0016 unpaired t-test). The affect is attributable to increased liver nicotinamide adenine dinucleotide (NADH) associated with ethanol metabolism in combination with NADH's role as a coenzyme in pyruvate-to-lactate conversion. Beyond studies of liver metabolism, this novel in vivo assay of changes in NADH levels makes hyperpolarized [1-(13)C]pyruvate a potentially viable substrate for studying the multiple in vivo metabolic pathways that use NADH (or NAD(+)) as a coenzyme, thus broadening the range of applications that have been discussed in the literature to date.
Keywords: Animals; Carbon Isotopes; Ethanol; Liver; Magnetic Resonance Spectroscopy; Male; Pyruvic Acid; Radiopharmaceuticals; Rats; Wistar

Increased perioculomotor urocortin 1 immunoreactivity in genetically selected alcohol preferring rats - Fonareva, Irina; Spangler, Erika; Cannella, Nazzareno; Sabino, Valentina; Cottone, Pietro; Ciccocioppo, Roberto; Zorrilla, Eric P.; Ryabinin, Andrey E. (Alcoholism, Clinical and Experimental Research, 2009)
INTRODUCTION: Urocortin 1 (Ucn 1) is an endogenous peptide related to the corticotropin-releasing factor (CRF). Ucn 1 is mainly expressed in the perioculomotor area (pIII), and its involvement in alcohol self-administration is well confirmed in mice. In other species, the relationship between the perioculomotor Ucn 1-containing population of neurons (pIIIu) and alcohol consumption needs further investigation. The pIII also has a significant subpopulation of dopaminergic neurons. Because of dopamine's (DA) role in addiction, it is important to evaluate whether this subpopulation of neurons contributes to addiction-related phenotypes. Furthermore, the effects of gender on the relationship between Ucn 1 and tyrosine hydroxylase (TH) in pIII and alcohol preference in rats have not been previously assessed. METHODS: To address these issues, we compared 2 Sardinian alcohol-preferring sublines of rats, a population maintained at the Scripps Research Institute (Scr:sP) and a population maintained at University of Camerino-Marchigian Sardinian preferring rats (msP), to corresponding nonselectively bred Wistar rats of both sexes. Ucn 1- and TH-positive cells were detected on coronal midbrain sections from 6- to 8-week-old alcohol-naïve animals using brightfield and fluorescent immunohistochemistry. Ucn 1- and TH-positive cells in pIII were counted in the perioculomotor area, averaged across 2 to 3 sets, and binned into 3 bregma levels. RESULTS: Results demonstrated increased average counts of Ucn 1-positive cells in the middle bregma level in preferring male rats compared to Wistar controls and no difference in TH-positive cell counts in pIII. In addition, fluorescent double labeling revealed no colocalization of Ucn 1-positive and TH-positive neurons. Ucn 1 but not TH distribution was influenced by gender with female animals expressing more Ucn 1-positive cells than male animals in the peak bregma level. CONCLUSIONS: These findings extend previous reports of increased Ucn 1-positive cell distribution in preferring lines of animals. They indicate that Ucn1 contributes to increased alcohol consumption across different species and that this contribution could be gender specific. The results also suggest that Ucn1 regulates positive reinforcing rather than aversive properties of alcohol and that these effects could be mediated by CRF(2) receptors, independent of direct actions of DA.
Keywords: Alcohol Drinking; Animals; dopamine; Female; Fluorescent Antibody Technique; Immunohistochemistry; Male; Motor Cortex; Oculomotor Muscles; Rats; Tyrosine 3-Monooxygenase; Urocortins; Wistar

A line of mice selected for high blood ethanol concentrations shows drinking in the dark to intoxication - Crabbe, John C.; Metten, Pamela; Rhodes, Justin S.; Yu, Chia-Hua; Brown, Lauren Lyon; Phillips, Tamara J.; Finn, Deborah A. (Biological Psychiatry, 2009)
BACKGROUND: Many animal models of alcoholism have targeted aspects of excessive alcohol intake (abuse) and dependence. In the rodent, models aimed at increasing alcohol self-administration have used genetic or environmental manipulations, or their combination. Strictly genetic manipulations (e.g., comparison of inbred strains or targeted mutants, selective breeding) have not yielded rat or mouse genotypes that will regularly and voluntarily drink alcohol to the point of intoxication. Although some behavioral manipulations (e.g., scheduling or limiting access to alcohol, adding a sweetener) will induce mice or rats to drink enough alcohol to become intoxicated, these typically require significant food or water restriction or a long time to develop. We report progress toward the development of a new genetic animal model for high levels of alcohol drinking. METHODS: High Drinking in the Dark (HDID-1) mice have been selectively bred for high blood ethanol concentrations (BEC, ideally exceeding 100 mg%) resulting from the ingestion of a 20% alcohol solution. RESULTS: After 11 generations of selection, more than 56% of the population now exceeds this BEC after a 4-hour drinking session in which a single bottle containing 20% ethanol is available. The dose of ethanol consumed also produced quantifiable signs of intoxication. CONCLUSIONS: These mice will be useful for mechanistic studies of the biological and genetic contributions to excessive drinking.
Keywords: Alcohol Drinking; Alcoholic Intoxication; Animal; Animals; Darkness; Disease Models; Ethanol; Female; Inbred Strains; Inbreeding; Male; Mice

MudPIT analysis: application to human heart tissue - Kline, Kelli G.; Wu, Christine C. (Methods in Molecular Biology (Clifton, N.J.), 2009)
Although two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) has been used as the standard proteomic approach for separating proteins in a complex mixture, this technique has many drawbacks. These include a limited molecular mass range, poor separation of highly acidic or basic proteins, and exclusion of the majority of membrane proteins from analysis. Considering the important functions of many membrane proteins, such as receptors, ion transporters, signal transducers, and cell adhesion proteins, it is increasingly important that these proteins are not excluded during the global proteomic analysis of cellular systems. Multidimensional Protein Identification Technology (MudPIT) offers a gel-free alternative to 2D-PAGE for the analysis of both membrane and soluble proteins.The goal of this chapter is to provide detailed methods for using MudPIT to profile both membrane and soluble proteins in complex unfractionated samples. Methods discussed will include tissue homogenization, sample preparation, MudPIT, data analysis, and an application for the analysis of unfractionated total tissue homogenate from human heart.
Keywords: Chromatography; Cyanogen Bromide; Electrophoresis; Formates; Gel; High Pressure Liquid; Humans; Membrane Proteins; Myocardium; Proteome; Proteomics; Trypsin; Two-Dimensional

Neurobiological mechanisms contributing to alcohol-stress-anxiety interactions - Silberman, Yuval; Bajo, Michal; Chappell, Ann M.; Christian, Daniel T.; Cruz, Maureen; Diaz, Marvin R.; Kash, Thomas; Lack, Anna K.; Messing, Robert O.; Siggins, George R.; Winder, Danny; Roberto, Marisa; et al. (Alcohol (Fayetteville, N.Y.), 2009)
This article summarizes the proceedings of a symposium that was presented at a conference entitled "Alcoholism and Stress: A Framework for Future Treatment Strategies." The conference was held in Volterra, Italy on May 6-9, 2008 and this symposium was chaired by Jeff L. Weiner. The overall goal of this session was to review recent findings that may shed new light on the neurobiological mechanisms that underlie the complex relationships between stress, anxiety, and alcoholism. Dr. Danny Winder described a novel interaction between D1 receptor activation and the corticotrophin-releasing factor (CRF) system that leads to an increase in glutamatergic synaptic transmission in the bed nucleus of the stria terminalis. Dr. Marisa Roberto presented recent data describing how protein kinase C epsilon, ethanol, and CRF interact to alter GABAergic inhibition in the central nucleus of the amygdala. Dr. Jeff Weiner presented recent advances in our understanding of inhibitory circuitry within the basolateral amygdala (BLA) and how acute ethanol exposure enhances GABAergic inhibition in these pathways. Finally, Dr. Brian McCool discussed recent findings on complementary glutamatergic and GABAergic adaptations to chronic ethanol exposure and withdrawal in the BLA. Collectively, these investigators have identified novel mechanisms through which neurotransmitter and neuropeptide systems interact to modulate synaptic activity in stress and anxiety circuits. Their studies have also begun to describe how acute and chronic ethanol exposure influence excitatory and inhibitory synaptic communication in these pathways. These findings point toward a number of novel neurobiological targets that may prove useful for the development of more effective treatment strategies for alcohol use disorders.
Keywords: alcoholism; Amygdala; Animals; Anxiety; Corticotropin-Releasing Hormone; Ethanol; GABA-B; gamma-Aminobutyric Acid; Humans; Protein Kinase C-epsilon; Psychological; Receptors; Stress; Synaptic Transmission

Nicotinic receptor ligands reduce ethanol intake by high alcohol-drinking HAD-2 rats - Bell, Richard L.; Eiler, Bill J. A.; Cook, Jason B.; Rahman, Shafiqur (Alcohol (Fayetteville, N.Y.), 2009)
Neuronal nicotinic acetylcholine receptors (nAChRs) are implicated in the reinforcing effects of many drugs of abuse, including ethanol. The present study examined the efficacy of cytisine, a nAChR partial agonist, and lobeline, a putative nAChR antagonist, on the maintenance of ethanol drinking by HAD-2 rats. Adult male HAD-2 rats were given access to ethanol (15 and 30%, with ad libitum access to water and food) 22 h/day for 12 weeks, beginning at 60 days of age, after which cytisine (0.0, 0.5, and 1.5 mg/kg) was tested for 3 consecutive days. The rats were given an 18-day washout period and were then tested with lobeline (0.0, 1.0, and 5.0 mg/kg) for 3 consecutive days. Ethanol intake was measured at 1, 4, and 22 h postinjection. Rats were injected intraperitoneally just before lights out (1200 h). There was a significant main effect of cytisine treatment on the second test day, with the 1.5 mg/kg dose significantly reducing ethanol intake at the 1- and 4-h time-points, relative to saline, and the 0.5 mg/kg dose inducing a significant reduction at the 4-h time-point. Conversely, lobeline treatment resulted in significant main effects of treatment for all three time-points within each test day, with the 5.0 mg/kg dose significantly reducing ethanol intake, relative to saline, at each time-point within each test day. These findings provide further evidence that activity at the nAChR influences ethanol intake and is a promising target for pharmacotherapy development for the treatment of alcohol dependence and relapse.
Keywords: Alcohol Drinking; alcoholism; Animals; Cystine; dopamine; Drinking; Ligands; Lobeline; Male; Nicotinic; Rats; Receptors

The NMDA Receptor and Alcohol Addiction - Ron, Dorit; Wang, Jun (Biology of the NMDA Receptor, 2009)
Alcohol addiction is a costly and detrimental chronic relapsing disorder, characterized by compulsive alcohol use despite the negative consequences; it is thought to be associated with aberrant learning and memory processes [1,2]. The NMDA-type glutamate receptor (NMDAR) plays an essential role in synaptic plasticity and learning and memory [3,4]. Not surprisingly, it is well established that the NMDAR is a major target of alcohol (ethanol) in the brain and has been implicated in ethanol-associated phenotypes such as tolerance, dependence, withdrawal, craving, and relapse [5,6]. This chapter focuses on studies elucidating molecular mechanisms that underlie ethanol’s actions on the NMDAR, and discusses the physiological and behavioral consequences of ethanol’s actions. Finally, we summarize information regarding the potential use of modulators of NMDAR function as medication to treat the adverse effects of alcoholism.

Pharmacogenetic treatments for drug addiction: cocaine, amphetamine and methamphetamine - Haile, Colin N.; Kosten, Thomas R.; Kosten, Therese A. (The American Journal of Drug and Alcohol Abuse, 2009)
BACKGROUND: Pharmacogenetics uses genetic variation to predict individual differences in response to medications and holds much promise to improve treatment of addictive disorders. OBJECTIVES: To review how genetic variation affects responses to cocaine, amphetamine, and methamphetamine and how this information may guide pharmacotherapy. METHODS: We performed a cross-referenced literature search on pharmacogenetics, cocaine, amphetamine, and methamphetamine. RESULTS: We describe functional genetic variants for enzymes dopamine-beta-hydroxylase (DbetaH), catechol-O-methyltransferase (COMT), and dopamine transporter (DAT1), dopamine D4 receptor, and brain-derived neurotrophic factor (BDNF). A single nucleotide polymorphism (SNP; C-1021T) in the DbetaH gene is relevant to paranoia associated with disulfiram pharmacotherapy for cocaine addiction. Individuals with variable number tandem repeats (VNTR) of the SLC6A3 gene 3'-untranslated region polymorphism of DAT1 have altered responses to drugs. The 10/10 repeat respond poorly to methylphenidate pharmacotherapy and the 9/9 DAT1 variant show blunted euphoria and physiological response to amphetamine. COMT, D4 receptor, and BDNF polymorphisms are linked to methamphetamine abuse and psychosis. CONCLUSIONS: Disulfiram and methylphenidate pharmacotherapies for cocaine addiction are optimized by considering polymorphisms affecting DbetaH and DAT1 respectively. Altered subjective effects for amphetamine in DAT1 VNTR variants suggest a 'protected' phenotype. SCIENTIFIC SIGNIFICANCE: Pharmacogenetic-based treatments for psychostimulant addiction are critical for successful treatment.
Keywords: Amphetamine; Amphetamine-Related Disorders; Cocaine-Related Disorders; Disulfiram; Dopamine Uptake Inhibitors; Enzyme Inhibitors; Humans; Methamphetamine; Methylphenidate; Pharmacogenetics; Polymorphism; Single Nucleotide

Presynaptic CRF1 receptors mediate the ethanol enhancement of GABAergic transmission in the mouse central amygdala - Nie, Zhiguo; Zorrilla, Eric P.; Madamba, Samuel G.; Rice, Kenner C.; Roberto, Marissa; Siggins, George Robert (TheScientificWorldJournal, 2009)
Corticotropin-releasing factor (CRF) is a 41-amino-acid neuropeptide involved in stress responses initiated from several brain areas, including the amygdala formation. Research shows a strong relationship between stress, brain CRF, and excessive alcohol consumption. Behavioral studies suggest that the central amygdala (CeA) is significantly involved in alcohol reward and dependence. We recently reported that the ethanol augmentation of GABAergic synaptic transmission in rat CeA involves CRF1 receptors, because both CRF and ethanol significantly enhanced the amplitude of evoked GABAergic inhibitory postsynaptic currents (IPSCs) in CeA neurons from wild-type (WT) and CRF2 knockout (KO) mice, but not in neurons of CRF1 KO mice. The present study extends these findings using selective CRF receptor ligands, gene KO models, and miniature IPSC (mIPSC) analysis to assess further a presynaptic role for the CRF receptors in mediating ethanol effects in the CeA. In whole-cell patch recordings of pharmacologically isolated GABAAergic IPSCs from slices of mouse CeA, both CRF and ethanol augmented evoked IPSCs in a concentration-dependent manner, with low EC50s. A CRF1 (but not CRF2) KO construct and the CRF1-selective nonpeptide antagonist NIH-3 (LWH-63) blocked the augmenting effect of both CRF and ethanol on evoked IPSCs. Furthermore, the new selective CRF1 agonist stressin1, but not the CRF2 agonist urocortin 3, also increased evoked IPSC amplitudes. Both CRF and ethanol decreased paired-pulse facilitation (PPF) of evoked IPSCs and significantly enhanced the frequency, but not the amplitude, of spontaneous miniature GABAergic mIPSCs in CeA neurons of WT mice, suggesting a presynaptic site of action. The PPF effect of ethanol was abolished in CeA neurons of CRF1 KO mice. The CRF1 antagonist NIH-3 blocked the CRF- and ethanol-induced enhancement of mIPSC frequency in CeA neurons. These data indicate that presynaptic CRF1 receptors play a critical role in permitting or mediating ethanol enhancement of GABAergic synaptic transmission in CeA, via increased vesicular GABA release, and thus may be a rational target for the treatment of alcohol abuse and alcoholism.
Keywords: Amygdala; Animals; Corticotropin-Releasing Hormone; Electrophysiology; Ethanol; gamma-Aminobutyric Acid; Inbred C57BL; Knockout; Male; Mice; Patch-Clamp Techniques; Receptors; Synaptic Transmission

Quantitative strategies to fuel the merger of discovery and hypothesis-driven shotgun proteomics - Kline, Kelli G.; Finney, Greg L.; Wu, Christine C. (Briefings in Functional Genomics and Proteomics, 2009)
The ultimate goal of most shotgun proteomic pipelines is the discovery of novel biomarkers to direct the development of quantitative diagnostics for the detection and treatment of disease. Differential comparisons of biological samples identify candidate peptides that can serve as proxys of candidate proteins. While these discovery approaches are robust and fairly comprehensive, they have relatively low throughput. When merged with targeted mass spectrometry, this pipeline can fuel hypothesis-driven studies and the development of novel diagnostics and therapeutics.

Reconstructing generalized logical networks of transcriptional regulation in mouse brain from temporal gene expression data - Song, Mingzhou Joe; Lewis, Chris K.; Lance, Eric R.; Chesler, Elissa J.; Yordanova, Roumyana Kirova; Langston, Michael A.; Lodowski, Kerrie H.; Bergeson, Susan E. (EURASIP journal on bioinformatics & systems biology, 2009)
Gene expression time course data can be used not only to detect differentially expressed genes but also to find temporal associations among genes. The problem of reconstructing generalized logical networks to account for temporal dependencies among genes and environmental stimuli from transcriptomic data is addressed. A network reconstruction algorithm was developed that uses statistical significance as a criterion for network selection to avoid false-positive interactions arising from pure chance. The multinomial hypothesis testing-based network reconstruction allows for explicit specification of the false-positive rate, unique from all extant network inference algorithms. The method is superior to dynamic Bayesian network modeling in a simulation study. Temporal gene expression data from the brains of alcohol-treated mice in an analysis of the molecular response to alcohol are used for modeling. Genes from major neuronal pathways are identified as putative components of the alcohol response mechanism. Nine of these genes have associations with alcohol reported in literature. Several other potentially relevant genes, compatible with independent results from literature mining, may play a role in the response to alcohol. Additional, previously unknown gene interactions were discovered that, subject to biological verification, may offer new clues in the search for the elusive molecular mechanisms of alcoholism.

Regression models of atlas appearance - Rohlfing, Torsten; Sullivan, Edith V.; Pfefferbaum, Adolf (Information Processing in Medical Imaging: Proceedings of the ... Conference, 2009)
Models of object appearance based on principal components analysis provide powerful and versatile tools in computer vision and medical image analysis. A major shortcoming is that they rely entirely on the training data to extract principal modes of appearance variation and ignore underlying variables (e.g., subject age, gender). This paper introduces an appearance modeling framework based instead on generalized multi-linear regression. The training of regression appearance models is controlled by independent variables. This makes it straightforward to create model instances for specific values of these variables, which is akin to model interpolation. We demonstrate the new framework by creating an appearance model of the human brain from MR images of 36 subjects. Instances of the model created for different ages are compared with average shape atlases created from age-matched sub-populations. Relative tissue volumes vs. age in models are also compared with tissue volumes vs. subject age in the original images. In both experiments, we found excellent agreement between the regression models and the comparison data. We conclude that regression appearance models are a promising new technique for image analysis, with one potential application being the representation of a continuum of mutually consistent, age-specific atlases of the human brain.
Keywords: Algorithms; Anatomic; Automated; Brain; Computer Simulation; Computer-Assisted; Humans; Image Enhancement; Image Interpretation; imaging; Magnetic Resonance Imaging; Models; Pattern Recognition; Reproducibility of Results; Sensitivity and Specificity; Subtraction Technique; Three-Dimensional

Reward processing by the opioid system in the brain - Le Merrer, Julie; Becker, Jérôme A. J.; Befort, Katia; Kieffer, Brigitte L. (Physiological Reviews, 2009)
The opioid system consists of three receptors, mu, delta, and kappa, which are activated by endogenous opioid peptides processed from three protein precursors, proopiomelanocortin, proenkephalin, and prodynorphin. Opioid receptors are recruited in response to natural rewarding stimuli and drugs of abuse, and both endogenous opioids and their receptors are modified as addiction develops. Mechanisms whereby aberrant activation and modifications of the opioid system contribute to drug craving and relapse remain to be clarified. This review summarizes our present knowledge on brain sites where the endogenous opioid system controls hedonic responses and is modified in response to drugs of abuse in the rodent brain. We review 1) the latest data on the anatomy of the opioid system, 2) the consequences of local intracerebral pharmacological manipulation of the opioid system on reinforced behaviors, 3) the consequences of gene knockout on reinforced behaviors and drug dependence, and 4) the consequences of chronic exposure to drugs of abuse on expression levels of opioid system genes. Future studies will establish key molecular actors of the system and neural sites where opioid peptides and receptors contribute to the onset of addictive disorders. Combined with data from human and nonhuman primate (not reviewed here), research in this extremely active field has implications both for our understanding of the biology of addiction and for therapeutic interventions to treat the disorder.
Keywords: Animals; Brain; Endorphins; Humans; Messenger; Opioid; Receptors; Reinforcement (Psychology); Reward; RNA; Substance-Related Disorders

Role of 5-Hydroxytryptamine2C Receptors in Ca2+-Dependent Ethanol Potentiation of GABA Release onto Ventral Tegmental Area Dopamine Neurons - Theile, Jonathan W.; Morikawa, Hitoshi; Gonzales, Rueben A.; Morrisett, Richard A. (The Journal of Pharmacology and Experimental Therapeutics, 2009)
Activation of ventral tegmental area (VTA)-dopaminergic (DA) neurons by ethanol has been implicated in the rewarding and reinforcing actions of ethanol. GABAergic transmission is thought to play an important role in regulating the activity of DA neurons. We have reported previously that ethanol enhances GABA release onto VTA-DA neurons in a brain slice preparation. Because intraterminal Ca2+ levels regulate neurotransmitter release, we investigated the roles of Ca2+-dependent mechanisms in ethanol-induced enhancement of GABA release. Acute ethanol enhanced miniature inhibitory postsynaptic current (mIPSC) frequency in the presence of the nonspecific voltage-gated Ca2+ channel inhibitor, cadmium chloride, even though basal mIPSC frequency was reduced by cadmium. Conversely, the inositol-1,4,5-triphosphate receptor inhibitor, 2-aminoethoxydiphenylborane, and the sarco/endoplasmic reticulum Ca2+ ATPase pump inhibitor, cyclopiazonic acid, eliminated the ethanol enhancement of mIPSC frequency. Recent studies suggest that the G protein-coupled receptor, 5-hydroxytryptamine (5-HT) 2C, may modulate GABA release in the VTA. Thus, we also investigated the role of 5-HT2C receptors in ethanol enhancement of GABAergic transmission. Application of 5-HT and the 5-HT2C receptor agonist, Ro-60-0175 [(αS)-6-chloro-5-fluoro-α-methyl-1H-indole-1-ethanamine fumarate], alone enhanced mIPSC frequency of which the latter was abolished by the 5-HT2C receptor antagonist, SB200646 [N-(1-methyl-5-indoyl)-N-(3-pyridyl)urea hydrochloride], and substantially diminished by cyclopiazonic acid. Furthermore, SB200646 abolished the ethanol-induced increase in mIPSC frequency and had no effect on basal mIPSC frequency. These observations suggest that an increase in Ca2+ release from intracellular stores via 5-HT2C receptor activation is involved in the ethanol-induced enhancement of GABA release onto VTA-DA neurons.

Schedule of passive ethanol exposure affects subsequent intragastric ethanol self-infusion - Fidler, Tara L.; Oberlin, Brandon G.; Struthers, Amanda M.; Cunningham, Christopher L. (Alcoholism, Clinical and Experimental Research, 2009)
BACKGROUND: Many studies have shown that chronic ethanol exposure can enhance later self-administration of ethanol, but only a few studies have identified critical parameters for such exposure. The present studies examined temporal and other parameters of chronic ethanol exposure on subsequent intragastric (IG) self-infusion of ethanol. METHODS: Sprague-Dawley rats implanted with IG catheters were passively infused with ethanol for 5 to 6 days and then allowed to self-infuse ethanol or water using a procedure in which infusions were contingent upon licking fruit-flavored solutions. Experiment 1 examined the time interval between consecutive periods of passive infusion (Massed Group: 12 hours vs. Spaced Group: 36 hours). Experiment 2 studied the interval between the final passive infusion and onset of self-infusion (12 vs. 36 hours). Finally, Experiment 3 tested the effect of inserting self-infusion days within the passive infusion phase. RESULTS: Passive ethanol exposure on consecutive days induced relatively large amounts of ethanol self-infusion (4.1 to 7.9 g/kg/d). Increasing the duration of the ethanol-free interval between periods of passive exposure to 36 hours significantly reduced ethanol self-infusion (2.2 g/kg/d; Exp. 1). The time delay between the last passive ethanol exposure and onset of self-infusion had no effect on self-infusion (Exp. 2). Moreover, inserting no-choice self-infusion days between the last few passive exposure days did not increase self-infusion (Exp. 3). CONCLUSIONS: Measurement of withdrawal signs indicated that Massed passive exposure produced stronger dependence than Spaced passive exposure, suggesting that enhanced ethanol self-infusion in Massed Groups might be explained by the opportunity for greater negative reinforcement by ethanol. Although enhanced negative reinforcement might also explain why the Massed Group showed a weaker aversion for the ethanol-paired flavor than the Spaced Group, this observation could also be explained by the development of greater tolerance to ethanol's aversive pharmacological effects in the Massed Group.
Keywords: Alcohol Drinking; Alcoholic Intoxication; Animals; Central Nervous System Depressants; Conditioning (Psychology); Dose-Response Relationship; Drug; Ethanol; Gastrointestinal; Intubation; Rats; Self Administration; Sprague-Dawley; Substance Withdrawal Syndrome

Site-specific microinjection of baclofen into the anterior ventral tegmental area reduces binge-like ethanol intake in male C57BL/6J mice - Moore, Eileen M.; Boehm, Stephen L. (Behavioral Neuroscience, 2009)
The GABAB agonist baclofen has been shown to alter ethanol intake in human and animal studies (E. M. Moore et al., 2007). GABA-subB receptors are located within the ventral tegmental area (VTA; A. Imperato & G. DiChiara, 1986) and therefore may be involved in modulating voluntary ethanol intake. The present study assessed the effects of baclofen in a variation on a new mouse model of binge-like ethanol intake that takes advantage of the nocturnal nature of this species (J. S. Rhodes, K. Best, J. K. Belknap, D. A. Finn, & J. C. Crabbe, 2005; J. S. Rhodes et al., 2007). Baclofen or saline was microinjected into the anterior or posterior VTA of male C57BL/6J mice. Immediately afterward, mice were presented with ethanol, water, or sugar water using the Drinking in the Dark model, a procedure of fluid administration for 2 hr, 3 hr into the dark cycle). Fluid intake was recorded at 30, 60, 90, and 120 min; retro-orbital sinus bloods were sampled upon termination of the 120-min ethanol access period. Baclofen reduced binge-like ethanol intake when microinjected into the anterior VTA, whereas posterior VTA microinjections did not alter ethanol intake. Baclofen had no effect on water or sugar water intake when administered to anterior or posterior VTA. These results add to the growing literature suggesting that GABA-subB receptor systems are important in the modulation of binge-like ethanol intake and suggest that the GABA-subB receptor system may have different roles in anterior versus posterior VTA.
Keywords: Alcohol Drinking; Analysis of Variance; Animal; Animals; Baclofen; Catheterization; Circadian Rhythm; Darkness; Dietary Sucrose; Disease Models; Drinking Behavior; Ethanol; GABA Agonists; GABA-B Receptor Agonists; Inbred C57BL; Male; Mice; Microinjections; Ventral tegmental area

Stress-related neuropeptides and alcoholism: CRH, NPY and beyond - Ciccocioppo, Roberto; Gehlert, Donald R.; Ryabinin, Andrey; Kaur, Simranjit; Cippitelli, Andrea; Thorsell, Annika; Lê, Anh D.; Hipskind, Philip A.; Hamdouchi, Chafiq; Lu, Jianliang; Hembre, Erik J.; Cramer, Jeffrey; et al. (Alcohol (Fayetteville, N.Y.), 2009)
This article summarizes the proceedings of a symposium held at the conference on “Alcoholism and Stress: A Framework for Future Treatment Strategies” in Volterra, Italy, May 6–9, 2008. Chaired by Markus Heilig and Roberto Ciccocioppo, this symposium offered a forum for the presentation of recent data linking neuropetidergic neurotransmission to the regulation of different alcohol related behaviours in animals and in humans. Dr. Donald Gehlert described the development of a new corticotrophin releasing factor (CRH) receptor 1 antagonist and showed its efficacy in reducing alcohol consumption and stress-induced relapse in different animal models of alcohol abuse. Dr. Andrey Ryabinin reviewed recent findings in his laboratory indicating a role of the urocortin 1 (Ucn) receptor system in the regulation of alcohol intake. Dr. Annika Thorsell showed data supporting the significance of the neuropetide Y (NPY) receptor system in the modulation of behaviours associated with a history of ethanol intoxication. Dr. Roberto Ciccocioppo focused his presentation on the nociceptin/orphanin FQ (N/OFQ) receptors as treatment targets for alcoholism. Finally, Dr. Markus Heilig showed recent preclinical and clinical evidence suggesting that neurokinin 1 (NK1) antagonism may represent a promising new treatment for alcoholism. Collectively, these investigators highlighted the significance of neuropeptidergic neurotransmission in the regulation of neurobiological mechanisms of alcohol addiction. Data also revealed the importance of these systems as treatment targets for the development of new medication for alcoholism.

Synaptic proteome changes in the superior frontal gyrus and occipital cortex of the alcoholic brain - Etheridge, Naomi; Lewohl, Joanne M.; Mayfield, R. Dayne; Harris, R. Adron; Dodd, Peter R. (Proteomics. Clinical applications, 2009)
Cognitive deficits and behavioral changes that result from chronic alcohol abuse are a consequence of neuropathological changes which alter signal transmission through the neural network. To focus on the changes that occur at the point of connection between the neural network cells, synaptosomal preparations from post-mortem human brain of six chronic alcoholics and six non-alcoholic controls were compared using 2D-DIGE. Functionally affected and spared regions (superior frontal gyrus, SFG, and occipital cortex, OC, respectively) were analyzed from both groups to further investigate the specific pathological response that alcoholism has on the brain. Forty-nine proteins were differentially regulated between the SFG of alcoholics and the SFG of controls and 94 proteins were regulated in the OC with an overlap of 23 proteins. Additionally, the SFG was compared to the OC within each group (alcoholics or controls) to identify region specific differences. A selection were identified by MALDI-TOF mass spectrometry revealing proteins involved in vesicle transport, metabolism, folding and trafficking, and signal transduction, all of which have the potential to influence synaptic activity. A number of proteins identified in this study have been previously related to alcoholism; however, the focus on synaptic proteins has also uncovered novel alcoholism-affected proteins. Further exploration of these proteins will illuminate the mechanisms altering synaptic plasticity, and thus neuronal signaling and response, in the alcoholic brain.

Validation of the Bayesian Alcoholism Test Compared to Single Biomarkers in Detecting Harmful Drinking - Korzec, Sanne; Korzec, Alex; Conigrave, Katherine; Gisolf, Janneke; Tabakoff, Boris (Alcohol and Alcoholism, 2009)

μ-Opioid Receptors Selectively Regulate Basal Inhibitory Transmission in the Central Amygdala: Lack of Ethanol Interactions - Kang-Park, Maeng-Hee; Kieffer, Brigitte L.; Roberts, Amanda J.; Roberto, Marisa; Madamba, Samuel G.; Siggins, George Robert; Moore, Scott D. (Journal of Pharmacology and Experimental Therapeutics, 2009)
Endogenous opioid systems are implicated in the actions of ethanol. For example, μ-opioid receptor (MOR) knockout (KO) mice self-administer less alcohol than the genetically intact counterpart wild-type (WT) mice (Roberts et al., 2000). MOR KO mice also exhibit less anxiety-like behavior than WT mice (Filliol et al., 2000). To investigate the neurobiological mechanisms underlying these behaviors, we examined the effect of ethanol in brain slices from MOR KO and WT mice using sharp-electrode and whole-cell patch recording techniques. We focused our study in the central nucleus of the amygdala (CeA) because it is implicated in alcohol drinking behavior and stress behavior. We found that the amplitudes of evoked inhibitory postsynaptic currents (IPSCs) or inhibitory postsynaptic potentials (IPSPs) were significantly greater in MOR KO mice than WT mice. In addition, the baseline frequencies of spontaneous and miniature GABAA receptor-mediated inhibitory postsynaptic currents were significantly greater in CeA neurons from MOR KO than WT mice. However, ethanol enhancements of evoked IPSP and IPSC amplitudes and the frequency of miniature IPSCs were comparable between WT and MOR KO mice. Baseline spontaneous and miniature excitatory postsynaptic currents (EPSCs) and ethanol effects on EPSCs were not significantly different between MOR KO and WT mice. Based on knowledge of CeA circuitry and projections, we hypothesize that the role of MOR- and GABA receptor-mediated mechanisms in CeA underlying reinforcing effects of ethanol operate independently, possibly through pathway-specific responses within CeA.

Accumbens Homer2 overexpression facilitates alcohol-induced neuroplasticity in C57BL/6J mice - Szumlinski, Karen K.; Ary, Alexis W.; Lominac, Kevin D.; Klugmann, Matthias; Kippin, Tod E. (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2008)
Homer proteins are integral components of the postsynaptic density that are necessary for alcohol-induced neuroplasticity within the nucleus accumbens (NAC). In this report, we describe the effects of chronic alcohol consumption upon NAC Homer expression and investigate the functional consequences of mimicking the alcohol-induced changes in Homer expression vis-à-vis alcohol-induced changes in NAC neurochemistry and behavior. Chronic alcohol consumption under continuous access (3 months; daily intake approximately 11.2+/-1.5 g/kg/day) produced a robust increase in NAC Homer2 protein levels that was apparent at 2 days, 2 weeks, and 2 months following withdrawal from alcohol drinking. The increased Homer2 expression was accompanied by a less enduring elevation in total mGluR1 and NR2b levels that were evident at 2 days and 2 weeks but not at the 2-month time point. Mimicking the alcohol-induced increase in Homer2 levels by viral transfection of NAC neurons in alcohol-preferring C57BL/6J inbred mice enhanced behavioral output for alcohol reinforcement and increased alcohol intake under both preprandial and postprandial conditions. Moreover, NAC Homer2 overexpression facilitated the expression of an alcohol-conditioned place preference, as well as the development of motor tolerance. Finally, NAC Homer2 overexpression facilitated NAC glutamate and dopamine release following an acute alcohol injection and augmented alcohol-induced dopamine and glutamate sensitization, but did not affect NAC gamma-aminobutyric acid levels. Thus, an upregulation in NAC mGluR-Homer2-N-methyl-D-aspartic acid receptor signaling appears to be an important molecular adaptation to alcohol that promotes neuroplasticity facilitating motivational drive for alcohol and the development of alcoholism-related behaviors.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Carrier Proteins; Central Nervous System Depressants; Conditioning; Ethanol; Gene Expression Regulation; Genetic; Green Fluorescent Proteins; Homer Scaffolding Proteins; Inbred C57BL; Male; Metabotropic Glutamate; Mice; Neuronal Plasticity; Nucleus Accumbens; Operant; Receptors; Reinforcement (Psychology); Time Factors; Transduction; Transgenic

Addictions biology: haplotype-based analysis for 130 candidate genes on a single array - Hodgkinson, Colin A.; Yuan, Qiaoping; Xu, Ke; Shen, Pei-Hong; Heinz, Elizabeth; Lobos, Elizabeth A.; Binder, Elizabeth B.; Cubells, Joe; Ehlers, Cindy L.; Gelernter, Joel; Mann, John; Riley, Brien; et al. (Alcohol and Alcoholism (Oxford, Oxfordshire), 2008)
AIMS: To develop a panel of markers able to extract full haplotype information for candidate genes in alcoholism, other addictions and disorders of mood and anxiety. METHODS: A total of 130 genes were haplotype tagged and genotyped in 7 case/control populations and 51 reference populations using Illumina GoldenGate SNP genotyping technology, determining haplotype coverage. We also constructed and determined the efficacy of a panel of 186 ancestry informative markers. RESULTS: An average of 1465 loci were genotyped at an average completion rate of 91.3%, with an average call rate of 98.3% and replication rate of 99.7%. Completion and call rates were lowered by the performance of two datasets, highlighting the importance of the DNA quality in high throughput assays. A comparison of haplotypes captured by the Addictions Array tagging SNPs and commercially available whole-genome arrays from Illumina and Affymetrix shows comparable performance of the tag SNPs to the best whole-genome array in all populations for which data are available. CONCLUSIONS: Arrays of haplotype-tagged candidate genes, such as this addictions-focused array, represent a cost-effective approach to generate high-quality SNP genotyping data useful for the haplotype-based analysis of panels of genes such as these 130 genes of interest to alcohol and addictions researchers. The inclusion of the 186 ancestry informative markers allows for the detection and correction for admixture and further enhances the utility of the array.
Keywords: Addictive; Alleles; Behavior; Case-Control Studies; Chromosome Mapping; Genome; Genotype; Haplotypes; Human; Humans; Polymorphism; Sequence Tagged Sites; Single Nucleotide

Alcohol trait and transcriptional genomic analysis of C57BL/6 substrains - Mulligan, M. K.; Ponomarev, I.; Boehm, S. L.; Owen, J. A.; Levin, P. S.; Berman, A. E.; Blednov, Y. A.; Crabbe, J. C.; Williams, R. W.; Miles, M. F.; Bergeson, S. E. (Genes, Brain, and Behavior, 2008)
C57BL/6 inbred mice have been widely used as research models; however, widespread demand has led to the creation of several B6 substrains with markedly different phenotypes. In this study, we report that two substrains of C57BL/6 mice, C57BL/6J (B6J) and C57BL/6NCrl (B6C), separated over 50 years ago at two different breeding facilities differ significantly in alcohol consumption and alcohol preference. The genomes of these two substrains are estimated to differ by only 1-2% of all gene loci, providing a unique opportunity to extract particular expression signatures between these substrains that are associated with quantifiable behavioral differences. Expression profiling of the cortex and striatum, hippocampus, cerebellum and the ventral brain region from alcohol-naïve B6C and B6J mice showed intervals on three chromosomes that are enriched in clusters of coregulated transcripts significantly divergent between the substrains. Additional analysis identified two genomic regions containing putative copy number differences between the substrains. One such region on chromosome 14 contained an estimated 3n copy number in the B6J genome compared with B6C. Within this interval, a gene of unknown function, D14Ertd449e, was found to be both associated with alcohol preference and vary in copy number across several inbred strain lineages. H2afz, Psen1, Wdfy1 and Clu were also identified as candidate genes that may be involved in influencing alcohol consumption.
Keywords: Alcohol Drinking; Alcohol-Induced Disorders; alcoholism; Animal; Animals; Brain; Brain Chemistry; Chromosome Mapping; Disease Models; DNA Mutational Analysis; Female; Gene Dosage; Gene Expression Profiling; Genetic; Genetic Predisposition to Disease; Genetic Testing; Genome; Genotype; Inbred C57BL; Male; Mice; Nervous System; Phenotype; Species Specificity; Transcription

Application of pressurized solvents for ultra fast trypsin hydrolysis in proteomics: Proteomics on the fly - López-Ferrer, Daniel; Petritis, Konstantinos; Hixson, Kim K.; Heibeck, Tyler H.; Moore, Ronald J.; Belov, Mikhail E.; Camp, David G.; Smith, Richard D. (Journal of proteome research, 2008)
A new method for rapid proteolytic digestion of proteins under high pressure that uses pressure cycling technology in the range of 5 to 35 kpsi was demonstrated for proteomic analysis. Successful in-solution digestions of single proteins and complex protein mixtures were achieved in 60 s and then analyzed by reversed phase liquid chromatography-electrospray ionization ion trap-mass spectrometry. Method performance in terms of the number of Shewanella oneidensis peptides and proteins identified in a shotgun approach was evaluated relative to a traditional “overnight” sample preparation method. Advantages of the new method include greatly simplified sample processing, easy implementation, no cross contamination among samples, and cost effectiveness.

ArrayPlex: distributed, interactive and programmatic access to genome sequence, annotation, ontology, and analytical toolsets - Killion, Patrick J.; Iyer, Vishwanath R. (Genome Biology, 2008)
ArrayPlex is a software package that centrally provides a large number of flexible toolsets useful for functional genomics, including microarray data storage, quality assessments, data visualization, gene annotation retrieval, statistical tests, genomic sequence retrieval and motif analysis. It uses a client-server architecture based on open source components, provides graphical, command-line, and programmatic access to all needed resources, and is extensible by virtue of a documented application programming interface. ArrayPlex is available at http://sourceforge.net/projects/arrayplex/.
Keywords: Genomics; Internet; Microarray Analysis; Software

Autonomic activation associated with ethanol self-administration in adult female P rats - Bell, Richard L.; Rodd, Zachary A.; Toalston, Jamie E.; McKinzie, David L.; Lumeng, Lawrence; Li, Ting-Kai; McBride, William J.; Murphy, James M. (Pharmacology, biochemistry, and behavior, 2008)
The present study examined changes in heart rate (HR) prior to and during limited access ethanol drinking in adult female P rats. P rats were implanted with radiotelemetric transmitters to measure HR. Daily testing involved a 90-min pre-test period (water only available) and a subsequent 90-min test period [either water (W) or ethanol available]. After a week of habituation, one ethanol group had access to ethanol for 7 weeks (CE), and another ethanol group had access for 4 weeks, was deprived for 2 weeks and then had access for a final week (DEP). Analyses of HR revealed that CE and DEP rats had significantly higher HR than W rats during test periods that ethanol was present and that DEP rats displayed higher HR during the early test period of the ethanol deprivation interval, as well. These data indicate that ethanol drinking induces HR activation in adult female P rats, and that this activation can be conditioned to the test cage environment, paralleling reports on contextual conditioning and cue-reactivity in alcoholics exposed to alcohol-associated stimuli. Therefore, this behavioral test may prove advantageous in screening pharmacotherapies for reducing craving and relapse, which are associated with cue-reactivity in abstinent alcoholics.

Brain regional Fos expression elicited by the activation of mu- but not delta-opioid receptors of the ventral tegmental area: evidence for an implication of the ventral thalamus in opiate reward - David, Vincent; Matifas, Audrey; Gavello-Baudy, Stéphanie; Decorte, Laurence; Kieffer, Brigitte L.; Cazala, Pierre (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2008)
Both mu-opioid receptors (MORs) and delta-opioid receptors (DORs) are expressed in the ventral tegmental area (VTA) and are thought to be involved in the addictive properties of opiates. However, their respective contributions to opiate reward remain unclear. We used intracranial self-administration (ICSA) to study the rewarding effects of morphine microinjections into the VTA of male and female MOR-/- and DOR-/- mice. In brains of mice tested for intra-VTA morphine self-administration, we analyzed regional Fos protein expression to investigate the neural circuitry underlying this behavior. Male and female WT and DOR-/- mice exhibited similar self-administration performances, whereas knockout of the MOR gene abolished intra-VTA morphine self-administration at all doses tested. Naloxone (4 mg/kg) disrupted this behavior in WT and DOR mutants, without triggering physical signs of withdrawal. Morphine ICSA was associated with an increase in Fos within the nucleus accumbens, striatum, limbic cortices, amygdala, hippocampus, the lateral mammillary nucleus (LM), and the ventral posteromedial thalamus (VPM). This latter structure was found to express high levels of Fos exclusively in self-administering WT and DOR-/- mice. Abolition of morphine reward in MOR-/- mice was associated with a decrease in Fos-positive neurons in the mesocorticolimbic dopamine system, amygdala, hippocampus (CA1), LM, and a complete absence within the VPM. We conclude that (i) VTA MORs, but not DORs, are critical for morphine reward and (ii) the role of VTA-thalamic projections in opiate reward deserves to be further explored.
Keywords: Analysis of Variance; Animal; Animals; Behavior; Brain; Cell Count; Conditioning; delta; Female; Gene Expression Regulation; Inbred C57BL; Knockout; Male; Mice; Morphine; mu; Naloxone; Narcotic Antagonists; Narcotics; Neurons; Oncogene Proteins v-fos; Operant; Opioid; Reaction Time; Receptors; Self Administration; Ventral tegmental area

Can serotonin transporter genotype predict serotonergic function, chronicity, and severity of drinking? - Johnson, Bankole A.; Javors, Martin A.; Roache, John D.; Seneviratne, Chamindi; Bergeson, Susan E.; Ait-Daoud, Nassima; Dawes, Michael A.; Ma, Jennie Z. (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2008)
Serotonin transporter (5-HTT) activity is greater in carriers of the long (L) vs. short (S) alleles of the 5-HTT-linked polymorphic region (5'-HTTLPR) among healthy control subjects but not alcohol-dependent adults. In 198 alcoholics, we determined the relationship between current or lifetime drinking and platelet 5-HTT function and density among allelic variants of the 5'-HTTLPR. SS subjects were younger than L-carriers (LL and LS) (p<0.0085) and had fewer years of lifetime drinking. For L-carriers, the mean of Bmax for paroxetine binding, but not Vmax for serotonin (5-HT) uptake, was lower than that for SS subjects (p<0.05). More L-carriers than their SS counterparts had Vmax for 5-HT uptake below 200 nmol/10(7) platelets-min (p<0.05) and Bmax for paroxetine binding below 600 nmol/mg protein (p<0.06). Current drinking (drinks per day during the past 14 days) correlated positively with Km and Vmax of platelet 5-HT uptake (p<0.05) and negatively with Bmax, but not Kd, of paroxetine binding (p<0.05) for L-carriers alone. Years of lifetime drinking correlated negatively with Km and Vmax of platelet 5-HT uptake (p<0.05) and B(max), but not Kd, of paroxetine binding (p<0.05) for L-carriers alone. Among L-carriers alone, there were higher levels of platelet 5-HT uptake and lower levels of platelet paroxetine binding with increased drinking, and more lifetime drinking was associated with modestly lower levels of 5-HT uptake and paroxetine binding. Thus, 5-HTT expression varies with current and lifetime drinking in L-carriers alone.
Keywords: Adolescent; Adult; Aged; alcoholism; Blood Platelets; Female; Genetic; Genotype; Humans; Male; Middle Aged; Paroxetine; Polymorphism; Predictive Value of Tests; Regression Analysis; Retrospective Studies; Serotonin; Serotonin Plasma Membrane Transport Proteins; Serotonin Uptake Inhibitors; Severity of Illness Index; Statistics as Topic

CARM1 promotes adipocyte differentiation by coactivating PPARgamma - Yadav, Neelu; Cheng, Donghang; Richard, Stephane; Morel, Melanie; Iyer, Vishwanath R.; Aldaz, C. Marcelo; Bedford, Mark T. (EMBO reports, 2008)
The coactivator-associated arginine methyltransferase 1 (CARM1) is recruited to gene promoters by many transcription factors. To identify new pathways that use CARM1, we carried out a comprehensive transcriptome analysis of CARM1-knockout embryos. By using complementary DNA microarrays and serial analysis of gene expression, we identified various genes involved in lipid metabolism that were underrepresented in CARM1-knockout embryos, indicating an important role for this coactivator in adipose tissue biology. We also observed that the amount of brown fat in CARM1-knockout embryos is reduced. Furthermore, cells lacking CARM1 have a severely curtailed potential to differentiate into mature adipocytes. Reporter experiments and chromatin immunoprecipitation analysis show that CARM1 regulates these processes by acting as a coactivator for peroxisome proliferator-activated receptor gamma (PPARgamma). Together, these results show that CARM1 promotes adipocyte differentiation by coactivating PPARgamma-mediated transcription and thus might be important in energy balance.
Keywords: 3T3-L1 Cells; Adipocytes; Adipose Tissue; Animals; Brown; Cell Differentiation; Embryo; Estrogens; Gene Expression Profiling; Genetic; Mammalian; Messenger; Mice; PPAR gamma; Protein-Arginine N-Methyltransferases; RNA; Transcription

Cellular and behavioral interactions of gabapentin with alcohol dependence - M., Roberto; N.W., Gilpin; L.E., O'Dell; T., Cruz M.; A.C., Morse; G.R., Siggins; G.F., Koob (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2008)
Gabapentin is a structural analogue of GABA that has anticonvulsant properties. Despite the therapeutic efficacy of gabapentin, its molecular and cellular mechanisms of action are unclear. The GABAergic system in the central nucleus of the amygdala (CeA) plays an important role in regulating voluntary ethanol intake. Here we investigated the effect of gabapentin on GABAergic transmission in CeA slices, on ethanol intake and on an anxiety measure, using animal models of ethanol dependence. Gabapentin increased the amplitudes of evoked GABA receptor-mediated inhibitory postsynaptic currents (GABA-IPSCs) in CeA neurons from non-dependent rats, but decreased their amplitudes in CeA of ethanol-dependent rats. Gabapentin effects were blocked in the presence of a specific GABAB receptor antagonist. The sensitivity of the GABA-IPSCs to a GABAB receptor antagonist and an agonist was decreased after chronic ethanol, suggesting that ethanol-induced neuroadaptations of GABAB receptors associated with ethanol dependence may account for the differential effects of gabapentin after chronic ethanol. Systemic gabapentin reduced ethanol intake in dependent, but not in non-dependent rats and reversed the anxiogenic-like effects of ethanol abstinence using an acute dependence model. Gabapentin infused directly into the CeA also blocked dependence-induced elevation in operant ethanol responding. Collectively, these findings show that gabapentin reverses behavioral measures of ethanol dependence, and in turn dependence reverses the effects of gabapentin on CeA neurons and suggest that gabapentin represents a potential medication for treatment of alcoholism.

Chromatographic benefits of elevated temperature for the proteomic analysis of membrane proteins - Blackler, Adele R.; Speers, Anna E.; Wu, Christine C. (Proteomics, 2008)
Integral membrane proteins (IMPs) perform crucial cellular functions and are the primary targets for most pharmaceutical agents. However, the hydrophobic nature of their membrane-embedded domains and their intimate association with lipids makes them difficult to handle. Multiple proteomics platforms that include LC separations have been reported for the high-throughput profiling of complex protein samples. However, there are still many challenges to overcome for proteomic analyses of IMPs, especially as compared to their soluble counterparts. In particular, considerations for the technical challenges associated with chromatographic separations are just beginning to be investigated. Here, we review the benefits of using elevated temperatures during LC for the proteomic analysis of complex membrane protein samples.

Comparison of the Distributions of Urocortin Containing and Cholinergic Neurons in the Perioculomotor Midbrain of the Cat and Macaque - May, Paul J.; Reiner, Anton J.; Ryabinin, Andrey E. (The Journal of comparative neurology, 2008)
Urocortin is a novel neurotransmitter that appears to play a role in eating and drinking behavior. Most urocortin-positive (urocortin+) neurons in rodents are found in the cytoarchitecturally defined Edinger-Westphal nucleus (EW). However, the EW is traditionally described as the source of the preganglionic parasympathetic outflow to the ciliary ganglion. We examined the distribution of urocortin+ cells and motoneurons by use of immunohistochemical staining for this peptide and for choline acetyl transferase (ChAT) in macaque monkeys, where most preganglionic motoneurons inhabit the EW, and in cats, where most do not. In both species, lack of overt double labeling indicated the ChAT+ and urocortin+ cells are separate populations. In the monkey, most non-oculomotor ChAT+ neurons were found within the EW. In contrast, urocortin+ cells were mainly distributed between the oculomotor nuclei, and in the supraoculomotor area. In the cat, most non-oculomotor ChAT+ cells were located in the supraoculomotor area and anteromedian nucleus. Few were present in the cat EW. Instead, this nucleus was filled with urocortin+ cells. These results highlight the fact the term EW has come to indicate different nuclei in different species. Consequently, we have adopted the identifiers preganglionic (EWPG) and urocortin containing (EWU) to designate the cytoarchitecturally defined EW nuclei in monkeys and cats, respectively. Furthermore, we propose a new open-ended nomenclature for the perioculomotor (pIII) cells groups that have distinctive projections and neurochemical signatures. This will allow more effective scientific discourse on the connections and function of groups like the periculomotor urocortin (pIIIU) and preganglionic (pIIIPG) populations.

Corticotropin-releasing factor-1 receptor involvement in behavioral neuroadaptation to ethanol: A urocortin1-independent mechanism - Pastor, Raúl; McKinnon, Carrie S.; Scibelli, Angela C.; Burkhart-Kasch, Sue; Reed, Cheryl; Ryabinin, Andrey E.; Coste, Sarah C.; Stenzel-Poore, Mary P.; Phillips, Tamara J. (Proceedings of the National Academy of Sciences, 2008)
A common expression of neuroadaptations induced by repeated exposure to addictive drugs is a persistent sensitized behavioral response to their stimulant properties. Neuroplasticity underlying drug-induced sensitization has been proposed to explain compulsive drug pursuit and consumption characteristic of addiction. The hypothalamic-pituitary-adrenal (HPA) axis-activating neuropeptide, corticotropin-releasing factor (CRF), may be the keystone in drug-induced neuroadaptation. Corticosterone-activated glucocorticoid receptors (GRs) mediate the development of sensitization to ethanol (EtOH), implicating the HPA axis in this process. EtOH-induced increases in corticosterone require CRF activation of CRF1 receptors. We posited that CRF1 signaling pathways are crucial for EtOH-induced sensitization. We demonstrate that mice lacking CRF1 receptors do not show psychomotor sensitization to EtOH, a phenomenon that was also absent in CRF1 + 2 receptor double-knockout mice. Deletion of CRF2 receptors alone did not prevent sensitization. A blunted endocrine response to EtOH was found only in the genotypes showing no sensitization. The CRF1 receptor antagonist CP-154,526 attenuated the acquisition and prevented the expression of EtOH-induced psychomotor sensitization. Because CRF1 receptors are also activated by urocortin-1 (Ucn1), we tested Ucn1 knockout mice for EtOH sensitization and found normal sensitization in this genotype. Finally, we show that the GR antagonist mifepristone does not block the expression of EtOH sensitization. CRF and CRF1 receptors, therefore, are involved in the neurobiological adaptations that underlie the development and expression of psychomotor sensitization to EtOH. A CRF/CRF1-mediated mechanism involving the HPA axis is proposed for acquisition, whereas an extrahypothalamic CRF/CRF1 participation is suggested for expression of sensitization to EtOH.
Keywords: 526; addiction; CP-154; HPA axis; Knockout mice; psychomotor sensitization

Differences in the urocortin 1 system between long-sleep and short-sleep mice - Turek, Victoria F.; Bennett, Beth; Ryabinin, Andrey E. (Genes, Brain, and Behavior, 2008)
There is evidence that the peptide urocortin 1 (Ucn1) may be involved in mediating some of the effects of ethanol. The purpose of the present study was to characterize Ucn1 immunoreactivity in mice selectively bred for either high or low sensitivity to ethanol-induced sedation, with additional differences in their response to ethanol-induced hypothermia. The brains of naïve male mice of the inbred long sleep/short sleep (ILS/ISS) selected lines were analyzed by immunohistochemistry. Significant differences were found between lines in the number of Ucn1-containing cells in the non-preganglionic Edinger-Westphal nucleus (npEW, the main source of Ucn1 in the brain); with the ISS mice having more cells. However, significant differences in the optical density of Ucn1 immunoreactivity in individual npEW cells and differences in cell area were also found between lines, with ILS mice having a greater density of Ucn1 per cell and having larger cells in the npEW. Importantly, the ILS mice also had a significantly greater number of Ucn1-positive terminal fibers than ISS mice in the lateral septum and the dorsal raphe nucleus, projection areas of Ucn1-containing neurons. These results suggest that the greater sensitivity of ILS than ISS mice to the hypothermic effects of ethanol could be mediated by stronger innervation of the dorsal raphe by Ucn1-containing fibers. In addition, these results lend further support to previous findings implicating Ucn1-containing projections from npEW to the dorsal raphe in ethanol-induced hypothermia.
Keywords: Animals; Body Temperature Regulation; Brain; Ethanol; Immunoenzyme Techniques; Inbred Strains; Male; Mice; Nerve Fibers; Neurons; Sleep; Urocortins

Differential gene expression in the nucleus accumbens with ethanol self-administration in inbred alcohol-preferring rats - Rodd, Zachary A.; Kimpel, Mark W.; Edenberg, Howard J.; Bell, Richard L.; Strother, Wendy N.; McClintick, Jeanette N.; Carr, Lucinda G.; Liang, Tiebing; McBride, William J. (Pharmacology, Biochemistry, and Behavior, 2008)
The current study examined the effects of operant ethanol (EtOH) self-administration on gene expression kin the nucleus accumbens (ACB) and amygdala (AMYG) of inbred alcohol-preferring (iP) rats. Rats self-trained on a standard two-lever operant paradigm to administer either water-water, EtOH (15% v/v)-water, or saccharin (SAC; 0.0125% g/v)-water. Animals were killed 24 h after the last operant session, and the ACB and AMYG dissected; RNA was extracted and purified for microarray analysis. For the ACB, there were 513 significant differences at the p<0.01 level in named genes: 55 between SAC and water; 215 between EtOH and water, and 243 between EtOH and SAC. In the case of the AMYG (p<0.01), there were 48 between SAC and water, 23 between EtOH and water, and 63 between EtOH and SAC group. Gene Ontology (GO) analysis indicated that differences in the ACB between the EtOH and SAC groups could be grouped into 15 significant (p<0.05) categories, which included major categories such as synaptic transmission, cell and ion homeostasis, and neurogenesis, whereas differences between the EtOH and water groups had only 4 categories, which also included homeostasis and synaptic transmission. Several genes were in common between the EtOH and both the SAC and water groups in the synaptic transmission (e.g., Cav2, Nrxn3, Gabrb2, Gad1, Homer1) and homeostasis (S100b, Prkca, Ftl1) categories. Overall, the results suggest that changes in gene expression in the ACB of iP rats are associated with the reinforcing effects of EtOH.
Keywords: alcoholism; Amygdala; Animals; Conditioning; Ethanol; Female; Gene Expression; Inbred Strains; Male; Models; Neurological; Nucleus Accumbens; Oligonucleotide Array Sequence Analysis; Operant; Psychological; Rats; Reverse Transcriptase Polymerase Chain Reaction; Saccharin; Self Administration

Dynamic remodeling of individual nucleosomes across a eukaryotic genome in response to transcriptional perturbation - Shivaswamy, Sushma; Bhinge, Akshay; Zhao, Yongjun; Jones, Steven; Hirst, Martin; Iyer, Vishwanath R. (PLoS biology, 2008)
The eukaryotic genome is packaged as chromatin with nucleosomes comprising its basic structural unit, but the detailed structure of chromatin and its dynamic remodeling in terms of individual nucleosome positions has not been completely defined experimentally for any genome. We used ultra-high-throughput sequencing to map the remodeling of individual nucleosomes throughout the yeast genome before and after a physiological perturbation that causes genome-wide transcriptional changes. Nearly 80% of the genome is covered by positioned nucleosomes occurring in a limited number of stereotypical patterns in relation to transcribed regions and transcription factor binding sites. Chromatin remodeling in response to physiological perturbation was typically associated with the eviction, appearance, or repositioning of one or two nucleosomes in the promoter, rather than broader region-wide changes. Dynamic nucleosome remodeling tends to increase the accessibility of binding sites for transcription factors that mediate transcriptional changes. However, specific nucleosomal rearrangements were also evident at promoters even when there was no apparent transcriptional change, indicating that there is no simple, globally applicable relationship between chromatin remodeling and transcriptional activity. Our study provides a detailed, high-resolution, dynamic map of single-nucleosome remodeling across the yeast genome and its relation to global transcriptional changes.
Keywords: Base Sequence; Binding Sites; Chromatin Assembly and Disassembly; DNA; Eukaryotic Cells; Genetic; Genome; Models; Molecular Sequence Data; Nucleosomes; Open Reading Frames; Promoter Regions; Saccharomyces cerevisiae; Sequence Analysis; TATA Box; Transcription; Transcription Factors; Transcription Initiation Site

Effects of short deprivation and re-exposure intervals on the ethanol drinking behavior of selectively bred high alcohol-consuming rats - Bell, Richard L.; Rodd, Zachary A.; Schultz, Jonathon A.; Peper, Caron L.; Lumeng, Lawrence; Murphy, James M.; McBride, William J. (Alcohol (Fayetteville, N.Y.), 2008)
Alcoholics generally display cycles of excessive ethanol intake, abstinence and relapse behavior. Using an animal model of relapse-like drinking, the alcohol deprivation effect (ADE), our laboratory has shown that repeated 2-week cycles of ethanol deprivation and re-exposure, following an initial 6 week access period, result in a robust ADE by alcohol-preferring (P) and high alcohol-drinking (HAD-1 and HAD-2) rats. These rat lines have been selectively bred to prefer a 10% ethanol solution over water. The present study examined whether P and HAD rats would display an ADE using much shorter ethanol deprivation and re-exposure intervals. Rats were given either continuous or periodic concurrent access to multiple concentrations [10%, 20%, and 30%, volume/volume (vol./vol.)] of ethanol. The periodic protocol involved access to ethanol for 12 days followed by 4 cycles of 4 days of deprivation and 4 days of re-exposure to ethanol access. HAD rats displayed a robust 24 hour ADE upon 1st re-exposure (HAD-1: ~ 5 vs. 8 g/kg/day; HAD-2: ~ 6 vs. 9 g/kg/day, baseline vs. re-exposure), whereas P rats (~ 7 vs. 8 g/kg/day) displayed a modest, nonsignificant, increase in 24 hour intake. In a separate group of rats, ethanol intake and blood alcohol concentrations (BACs) after the 1st hour of the 4th re-exposure cycle were HAD-1: 2.0 g/kg and 97 mg%, HAD-2: 2.3 g/kg and 73 mg%, and P: 1.2 g/kg and 71 mg%; with all three lines displaying a robust 1st hour ADE. These findings suggest that (a) an ADE may be observed with short ethanol deprivation and re-exposure intervals in HAD rats, and (b) the genetic make-up of the P and HAD rats influences the expression of this ADE.

Ethanol drinking in rodents: is free-choice drinking related to the reinforcing effects of ethanol? - Green, Alexis S.; Grahame, Nicholas J. (Alcohol (Fayetteville, N.Y.), 2008)
Many studies have used voluntary ethanol consumption by animals to assess the influence of genetic and environmental manipulations on ethanol drinking. However, the relationship between home cage ethanol consumption and more formal assessments of ethanol-reinforced behavior using operant and instrumental conditioning procedures is not always clear. The present review attempted to evaluate whether there are consistent correlations between mouse and rat home cage ethanol drinking on the one hand, and either operant oral self-administration (OSA), conditioned taste aversion (CTA), or conditioned place preference (CPP) with ethanol on the other. We also review literature on intravenous ethanol self-administration (IVSA). To collect data, we evaluated a range of genetic manipulations that can change both genes and ethanol drinking behavior including selective breeding, transgenic and knockout models, and inbred and recombinant inbred strain panels. For a genetic model to be included in the analysis, there had to be published data resulting in differences on home cage drinking and data for at least one of the other behavioral measures. A consistent, positive correlation was observed between ethanol drinking and OSA, suggesting that instrumental behavior is closely genetically related to consummatory and ingestive behavior directed at ethanol. A negative correlation was observed between CTA and drinking, suggesting that ethanol's aversive actions may limit oral consumption of ethanol. A more modest, positive relationship was observed between drinking and CPP, and there were not enough studies available to determine a relationship with IVSA. That some consistent outcomes were observed between widely disparate behavioral procedures and genetic populations may increase confidence in the validity of findings from these assays. These findings may also have important implications when researchers decide which phenotypes to use in measuring alcohol-reward relevant behaviors in novel animal models.
Keywords: Alcohol Drinking; Animal; Animals; Classical; Conditioning; Mice; Models; Operant; Rats; Reinforcement (Psychology); Self Administration

Ethanol Enhances GABAergic Transmission Onto Dopamine Neurons in the Ventral Tegmental Area of the Rat - Theile, Jonathan W.; Morikawa, Hitoshi; Gonzales, Reuben A.; Morrisett, Richard A. (Alcoholism, clinical and experimental research, 2008)
Background Activation of the dopaminergic (DA) neurons of the ventral tegmental area (VTA) by ethanol has been implicated in its rewarding and reinforcing effects. At most central synapses, ethanol generally increases inhibitory synaptic transmission; however, no studies have explored the effect of acute ethanol on GABAergic transmission in the VTA. Methods Whole-cell patch clamp recordings of inhibitory postsynaptic currents (IPSCs) from VTA-DA neurons in midbrain slices from young rats. Results Acute exposure of VTA-DA neurons to ethanol (25 to 50 mM) robustly enhanced GABAergic spontaneous and miniature IPSC frequency while inducing a slight enhancement of spontaneous IPSC (sIPSC) amplitude. Ethanol (50 mM) enhanced paired-pulse depression of evoked IPSCs, further suggesting enhanced GABA release onto VTA-DA neurons. The frequency of sIPSCs was suppressed by the GABAB agonist, baclofen (1.25 μM) and enhanced by the antagonist, SCH50911 (20 μM); however, neither appeared to modulate or occlude the effects of ethanol on sIPSC frequency. Conclusions The present results indicate that ethanol increases postsynaptic GABAA receptor sensitivity, enhances action potential-independent GABA release onto VTA-DA neurons, and that this latter effect is independent of GABAB auto-receptor inhibition of GABA release.

Ethanol Intake Patterns in Female Mice: Influence of Allopregnanolone and the Inhibition of Its Synthesis - Ford, Matthew M.; Beckley, Ethan H.; Nickel, Jeffrey D.; Eddy, Sarah; Finn, Deborah A. (Drug and alcohol dependence, 2008)
The neurosteroid allopregnanolone (ALLO) is a positive modulator of GABAA receptors that exhibits a psychopharmacological profile similar to ethanol (i.e., anxiolytic, sedative-hypnotic). Based on research suggesting that manipulation of ALLO levels altered ethanol self-administration in male rodents, the current studies determined whether exogenous ALLO administration or the inhibition of its synthesis in vivo modulated ethanol intake patterns in female C57BL/6J mice. Lickometer circuits collected temporal lick records of ethanol (10% v/v) and water consumption during daily 2-hr limited access sessions. Following the establishment of stable ethanol intake, studies examined the effect of an acute ALLO challenge (3.2 – 24.0 mg/kg) or a 7-day blockade of ALLO production with finasteride (FIN; 50 or 100 mg/kg) on ethanol intake in a within-subjects design. In contrast to results in male mice, ethanol dose (g/kg), ethanol preference, and most of the bout parameters were unaltered by ALLO pretreatment in female mice. Ethanol intake in females also was recalcitrant to 7-day treatment with 50 mg/kg FIN, whereas 100 mg/kg FIN significantly reduced the ethanol dose consumed by 35%. The FIN-attenuated ethanol intake was attributable to a significant decrease in bout frequency (up to 45%), with lick patterns indicating reduced maintenance of consumption throughout the 2-hr session. FIN also produced a dose-dependent decrease in brain ALLO levels. In conjunction with data in male mice, the present findings indicate that there are sex differences in the physiological regulation of ethanol intake patterns by GABAergic neurosteroids.

Ethanol potentiates dopamine uptake and increases cell surface distribution of dopamine transporters expressed in SK-N-SH and HEK-293 cells - Riherd, D. Nicole; Galindo, David G.; Krause, Lucretia R.; Mayfield, R. Dayne (Alcohol (Fayetteville, N.Y.), 2008)
Ethanol increases dopaminergic release in the reward and reinforcement areas of the brain. The primary protein responsible for terminating dopamine (DA) neurotransmission is the plasma membrane-bound dopamine transporter (DAT). In vitro electrophysiological and biochemical studies in Xenopus laevis oocytes have previously shown ethanol potentiates DAT function and increases transporter-binding sites. The potentiating effect of ethanol on the transporter is eliminated in Xenopus oocytes by the DAT mutation glycine 130 to threonine. However, ethanol's action on DAT functional regulation has yet to be examined in mammalian cell expression systems. To further understand the molecular mechanisms of ethanol's action on DAT, we determined the direct mechanistic action of short-term (< or =2 h) ethanol exposure on transporter function and cell surface distribution in non-neuronal human embryonic kidney cells-293 (HEK-293) and neuronal SK-N-SH neuroblastoma cells expressing the transporter. Wild-type or G130T mutant DAT were overexpressed in HEK-293 and SK-N-SH cells. Ethanol potentiated DAT mediated [(3)H]DA uptake in a dose (25, 50, 100 mM), but not time dependent manner in cells expressing wild-type DAT. Ethanol-induced potentiation of uptake was significantly reduced in cells expressing the G130T mutant. Analysis of DA uptake kinetic parameters indicates 100-mM ethanol exposure increased [(3)H]DA uptake velocity (V(max)), while affinity for DA (K(m)) remained unchanged. The effect of ethanol on wild-type DAT surface expression was measured by biotinylation cell surface labeling. DAT surface expression increased 40%-50% after 1-h, 100-mM ethanol exposure. These studies show ethanol potentiates DAT functional regulation in both neuronal and non-neuronal cells, suggesting a direct mechanistic action of ethanol on transporter trafficking in mammalian systems. Our findings demonstrate ethanol's action on DAT function and regulation is consistent across multiple model systems.
Keywords: Active; Biological Transport; Cell Line; dopamine; Dopamine Plasma Membrane Transport Proteins; Drug Synergism; Ethanol; Humans; Kidney; Neuroblastoma; Tumor

Ethanol's molecular targets - Harris, R. Adron; Trudell, James R.; Mihic, S. John (Science Signaling, 2008)
Ethanol produces a wide variety of behavioral and physiological effects in the body, but exactly how it acts to produce these effects is still poorly understood. Although ethanol was long believed to act nonspecifically through the disordering of lipids in cell membranes, proteins are at the core of most current theories of its mechanisms of action. Although ethanol affects various biochemical processes such as neurotransmitter release, enzyme function, and ion channel kinetics, we are only beginning to understand the specific molecular sites to which ethanol molecules bind to produce these myriad effects. For most effects of ethanol characterized thus far, it is unknown whether the protein whose function is being studied actually binds ethanol, or if alcohol is instead binding to another protein that then indirectly affects the functioning of the protein being studied. In this Review, we describe criteria that should be considered when identifying alcohol binding sites and highlight a number of proteins for which there exists considerable molecular-level evidence for distinct ethanol binding sites.
Keywords: Alcohol Drinking; Alcoholic Intoxication; Animals; Binding Sites; Cell Membrane; Drug Tolerance; Ethanol; GABA; Gene Expression Regulation; Humans; Ion Channels; Kinetics; Membrane Lipids; Protein Binding; Proteins; Receptors

Expression Quantitative Trait Loci and The Phenogen Database - Saba, Laura; Hoffman, Paula L.; Hornbaker, Cheryl; Bhave, Sanjiv V.; Tabakoff, Boris (Alcohol Research & Health, 2008)

GABAA receptors and alcohol - Lobo, Ingrid A.; Harris, R. Adron (New Insights Into the Function of GABAA Receptor Subtypes, 2008)
There is substantial evidence that GABAergic neurotransmission is important for many behavioral actions of ethanol and there are reports spanning more than 30 years of literature showing that low to moderate (3–30 mM) concentrations of ethanol enhance GABAergic neurotransmission. A key question is which GABA receptor subunits are sensitive to low concentrations of ethanol in vivo and in vitro. Recent evidence points to a role for extrasynaptic receptors. Another question is which behavioral actions of alcohol result from enhancement of GABAergic neurotransmission. Some clues are beginning to emerge from studies of knock-out and knock-in mice and from genetic analysis of human alcoholics. These approaches are converging on a role for GABAergic actions in regulating alcohol consumption and, perhaps, the development of alcoholism.
Keywords: alcohol; GABA; Receptor

Galanin alters GABAergic neurotransmission in the dorsal raphe nucleus - Sharkey, Lisa M.; Madamba, Samuel G.; Siggins, George R.; Bartfai, Tamas (Neurochemical Research, 2008)
The neuropeptide galanin and its three receptor subtypes (Gal R1-3) are highly expressed in the dorsal raphe nucleus (DRN), a region of the brain that contains a large population of serotonergic neurons. Galanin is co-expressed with serotonin in approximately 40% of the DRN neurons, and galanin and GALR2 expression are elevated by antidepressants like the SSRI fluoxetine, suggesting an interaction between serotonin and galanin. The present study examines the effect of galanin (Gal 1-29), a pan ligand for GalR (1-3) and the GalR2/GalR3-selective ligand, Gal 2-11, on the electrophysiological properties of DRN serotonergic neurons in a slice preparation. We recorded from cells in the DRN with electrophysiological characteristics consistent with those of serotonergic neurons that exhibit high input resistance, large after-hyperpolarizations and long spike duration as defined by Aghajanian and Vandermaelen. Both Gal 1-29 and Gal 2-11 decreased the amplitudes pharmacologically-isolated GABAergic inhibitory postsynaptic potentials (IPSPs) in these putative serotonergic neurons. Furthermore, based on paired pulse facilitation studies, we show that Gal 1-29 likely decreases GABA release through a presynaptic mechanism, whereas Gal 2-11 may act postsynaptically. These findings may enhance understanding of the cellular mechanisms underlying the effects of antidepressant treatments on galanin and galanin receptors in DRN.
Keywords: Animals; Galanin; gamma-Aminobutyric Acid; In Vitro Techniques; Male; Raphe Nuclei; Rats; Sprague-Dawley; Synaptic Transmission

Gene expression is altered in the lateral hypothalamus upon activation of the mu opioid receptor - Befort, K.; Filliol, D.; Darcq, E.; Ghate, A.; Matifas, A.; Lardenois, A.; Muller, J.; Thibault, C.; Dembele, D.; Poch, O.; Kieffer, B. L. (Annals of the New York Academy of Sciences, 2008)
The lateral hypothalamus (LH) is a brain structure that controls hedonic properties of both natural rewards and drugs of abuse. Mu opioid receptors are known to mediate drug reward, but whether overstimulation of these receptors impacts on LH function has not been studied. Here we have used a genome-wide microarray approach to identify LH responses to chronic mu opioid receptor activation at the transcriptional level. We have subjected wild-type and mu opioid receptor knockout mice to an escalating morphine regimen, which produces severe physical dependence in wild-type but not mutant animals. We have analyzed gene profiles in LH samples using the 430A.2 Affymetrix array and identified a set of 25 genes whose expression is altered by morphine in wild-type mice only. The regulation was confirmed for a subset of these genes using real-time quantitative PCR on samples from independent treatments. Altered expression of aquaporin 4, apolipoprotein D, and prostaglandin synthase is indicative of modified LH physiology. The regulation of two signaling genes (the serum glucocorticoid kinase and the regulator of G protein signaling 4) suggests that neurotransmission is altered in LH circuitry. Finally, the downregulation of apelin may indicate a potential role for this neuropeptide in opioid signaling and hedonic homeostasis. Altogether, our study shows that chronic mu opioid receptor stimulation induces gene expression plasticity in the LH and provides a unique collection of mu opioid receptor-dependent genes that potentially contribute to alter reward processes in addictive diseases.
Keywords: Animals; Gene Expression Regulation; hypothalamus; Inbred C57BL; Knockout; Male; Mice; Morphine; mu; Opioid; Polymerase Chain Reaction; Receptors; Reproducibility of Results

Genetic factors influencing alcohol dependence - Mayfield, R D; Harris, R A; Schuckit, M A (British Journal of Pharmacology, 2008)
Plentiful data from both animal and human studies support the importance of genetic influences in substance abuse and dependence (Bierut et al., 1998; Tsuang et al., 1998; Kendler et al., 2003). This review summarizes the evidence supporting such genetic influences, places them into perspective regarding animal and human studies, discusses the importance of both genes and environment, and highlights some specific genes of interest regarding the vulnerabilities for problems associated with alcohol use disorders. A long history of repetitive heavy use of alcohol exists across generations as well as the high prevalence of alcohol-related problems in Western societies. Moreover, the information offered here addresses the importance of more general issues regarding genetics and gene expression related to alcohol abuse and dependence.

The genomic determinants of alcohol preference in mice - Tabakoff, Boris; Saba, Laura; Kechris, Katherina; Hu, Wei; Bhave, Sanjiv V.; Finn, Deborah A.; Grahame, Nicholas J.; Hoffman, Paula L. (Mammalian Genome: Official Journal of the International Mammalian Genome Society, 2008)
Searches for the identity of genes that influence the levels of alcohol consumption by humans and other animals have often been driven by presupposition of the importance of particular gene products in determining positively or negatively reinforcing effects of ethanol. We have taken an unbiased approach and performed a meta-analysis across three types of mouse populations to correlate brain gene expression with levels of alcohol intake. Our studies, using filtering procedures based on QTL analysis, produced a list of eight candidate genes with highly heritable expression, which could explain a significant amount of the variance in alcohol preference in mice. Using the Allen Brain Atlas for gene expression, we noted that the candidate genes' expression was localized to the olfactory and limbic areas as well as to the orbitofrontal cortex. Informatics techniques and pathway analysis illustrated the role of the candidate genes in neuronal migration, differentiation, and synaptic remodeling. The importance of olfactory cues, learning and memory formation (Pavlovian conditioning), and cortical executive function, for regulating alcohol intake by animals (including humans), is discussed.
Keywords: Alcohol Drinking; Animals; Brain; Chromosome Mapping; Food Preferences; Gene Expression Profiling; Inbred C57BL; Inbred DBA; Inbred Strains; Male; Meta-Analysis as Topic; Mice; Oligonucleotide Array Sequence Analysis; Polymorphism; Quantitative Trait Loci; Single Nucleotide

Genomic insights into acute alcohol tolerance - Hu, Wei; Saba, Laura; Kechris, Katherina; Bhave, Sanjiv V.; Hoffman, Paula L.; Tabakoff, Boris (The Journal of Pharmacology and Experimental Therapeutics, 2008)
Alcohol "sensitivity" has been proposed as a predictive factor for development of alcohol dependence (Schuckit et al., 2005). Most measures of alcohol sensitivity in humans and animals include a component that can be ascribed to acute functional tolerance (AFT). AFT is a form of tolerance that develops within a single period of alcohol exposure and has a genetic component. We used microarray technology as well as quantitative trait locus analysis of phenotypic and gene expression data across 30 BXD recombinant inbred strains of mice, 20 inbred strains of mice, and two replicate lines of mice selectively bred for differences in AFT, to identify differentially expressed candidate genes that contribute to predisposition to AFT. Eight candidate genes were identified by our statistical and filtering methods. The location of brain expression of these genes was mapped using the Allen Brain Atlas (http://www.brain-map.org), and the transcript location and molecular pathway analysis indicated that brain structures and biochemical pathways implicated in long-term potentiation and memory might also participate in the generation of acute functional alcohol tolerance.
Keywords: Alcohol Drinking; alcoholism; Animals; Brain; Drug Tolerance; Ethanol; Genomics; Inbred BALB C; Inbred C3H; Inbred C57BL; Inbred CBA; Inbred DBA; Inbred Strains; Male; Mice; Quantitative Trait Loci

Global Identification of Myc Target Genes Reveals Its Direct Role in Mitochondrial Biogenesis and Its E-Box Usage In Vivo - Kim, Jonghwan; Lee, Ji-hoon; Iyer, Vishwanath R. (PLOS ONE, 2008)
The Myc oncoprotein is a transcription factor involved in a variety of human cancers. Overexpression of Myc is associated with malignant transformation. In normal cells, Myc is induced by mitotic signals, and in turn, it regulates the expression of downstream target genes. Although diverse roles of Myc have been predicted from many previous studies, detailed functions of Myc targets are still unclear. By combining chromatin immunoprecipitation (ChIP) and promoter microarrays, we identified a total of 1469 Myc direct target genes, the majority of which are novel, in HeLa cells and human primary fibroblasts. We observed dramatic changes of Myc occupancy at its target promoters in foreskin fibroblasts in response to serum stimulation. Among the targets of Myc, 107 were nuclear encoded genes involved in mitochondrial biogenesis. Genes with important roles in mitochondrial replication and biogenesis, such as POLG, POLG2, and NRF1 were identified as direct targets of Myc, confirming a direct role for Myc in regulating mitochondrial biogenesis. Analysis of target promoter sequences revealed a strong preference for Myc occupancy at promoters containing one of several described consensus sequences, CACGTG, in vivo. This study thus sheds light on the transcriptional regulatory networks mediated by Myc in vivo.
Keywords: Biosynthesis; Cell binding; Fibroblasts; Gene Expression; HeLa Cells; Mitochondria; Sequence Analysis; Sequence motif analysis

High quality catalog of proteotypic peptides from human heart - Kline, Kelli G.; Frewen, Barbara; Bristow, Michael R.; MacCoss, Michael J.; Wu, Christine C. (Journal of Proteome Research, 2008)
Proteomics research is beginning to expand beyond the more traditional shotgun analysis of protein mixtures to include targeted analyses of specific proteins using mass spectrometry. Integral to the development of a robust assay based on targeted mass spectrometry is prior knowledge of which peptides provide an accurate and sensitive proxy of the originating gene product (i.e., proteotypic peptides). To develop a catalog of "proteotypic peptides" in human heart, TRIzol extracts of left-ventricular tissue from nonfailing and failing human heart explants were optimized for shotgun proteomic analysis using Multidimensional Protein Identification Technology (MudPIT). Ten replicate MudPIT analyses were performed on each tissue sample and resulted in the identification of 30 605 unique peptides with a q-value < or = 0.01, corresponding to 7138 unique human heart proteins. Experimental observation frequencies were assessed and used to select over 4476 proteotypic peptides for 2558 heart proteins. This human cardiac data set can serve as a public reference to guide the selection of proteotypic peptides for future targeted mass spectrometry experiments monitoring potential protein biomarkers of human heart diseases.
Keywords: Biological; Heart; Heart Ventricles; Humans; Models; Myocardium; Organ Culture Techniques; Peptides; Proteome; Proteomics

Homers regulate drug-induced neuroplasticity: Implications for addiction - Szumlinski, Karen K.; Ary, Alexis W.; Lominac, Kevin D. (Biochemical pharmacology, 2008)
Drug addiction is a chronic, relapsing disorder, characterized by an uncontrollable motivation to seek and use drugs. Converging clinical and preclinical observations implicate pathologies within the corticolimbic glutamate system in the genetic predisposition to, and the development of, an addicted phenotype. Such observations pose cellular factors regulating glutamate transmission as likely molecular candidates in the etiology of addiction. Members of the Homer family of proteins regulate signal transduction through, and the trafficking of, glutamate receptors, as well as maintain and regulate extracellular glutamate levels in corticolimbic brain regions. This review summarizes the existing data implicating the Homer family of protein in acute behavioral and neurochemical sensitivity to drugs of abuse, the development of drug-induced neuroplasticity, as well as other behavioral and cognitive pathologies associated with an addicted state.

Inhibition of 5α-Reduced Steroid Biosynthesis Impedes Acquisition of Ethanol Drinking in Male C57BL/6J Mice - Ford, Matthew M.; Yoneyama, Naomi; Strong, Moriah N.; Fretwell, Andrea; Tanchuck, Michelle; Finn, Deborah A. (Alcoholism: Clinical and Experimental Research, 2008)
Background:  Allopregnanolone (ALLO) is a physiologically relevant neurosteroid modulator of GABAA receptors, and it exhibits a psychopharmacological profile that closely resembles the post-ingestive effects of ethanol. The 5α-reductase inhibitor finasteride (FIN), which inhibits biosynthesis of ALLO and structurally related neurosteroids, was previously demonstrated to reduce the maintenance of limited-access ethanol consumption. The primary aim of the current work was to determine whether FIN would reduce the acquisition of drinking in ethanol-naïve mice. Methods:  Male C57BL/6J (B6) mice were acclimated to a reverse light/dark schedule, and were provided ad libitum access to chow and water. Following habituation to vehicle injections (VEH; 20% w/v β-cyclodextrin; i.p.) administered 22-hour prior to drinking sessions with water only, mice were divided into 3 treatment groups: vehicle control (VEH), 50 mg/kg FIN (FIN-50), and 100 mg/kg FIN (FIN-100). Twenty-two hours after the first treatment, mice were permitted the inaugural 2-hour limited access to a 10% v/v ethanol solution (10E) and water. The acquisition of 10E consumption and underlying drinking patterns were assessed during FIN treatment (7 days) and subsequent FIN withdrawal (13 days) phases. Results:  FIN dose-dependently blocked the acquisition of 10E drinking and prevented the development of ethanol preference, thereby suggesting that the GABAergic neurosteroids may be important in the establishment of stable drinking patterns. FIN-elicited reductions in 10E intake were primarily attributable to selective and marked reductions in bout frequency, as no changes were observed in bout size, duration, or lick rates following FIN treatment. FIN-treated mice continued to exhibit attenuated ethanol consumption after 2 weeks post-treatment, despite a full recovery in brain ALLO levels. A second study confirmed the rightward and downward shift in the acquisition of ethanol intake following 7 daily FIN injections. While there were no significant group differences in brain ALLO levels following the seventh day of ethanol drinking, ALLO levels were decreased by 28% in the FIN-50 group. Conclusions:  Although the exact mechanism is unclear, FIN and other pharmacological interventions that modulate the GABAergic system may prove useful in curbing ethanol intake acquisition in at-risk individuals.
Keywords: alcohol; Allopregnanolone; Drinking Patterns; Finasteride; GABAA Receptors; Neurosteroid Metabolism

Involvement of JNK/p73/NOXA in vitamin E analog-induced apoptosis of human breast cancer cells - Wang, Pei; Yu, Weiping; Hu, Zhanzhi; Jia, Li; Iyer, Vishwanath R.; Sanders, Bob G.; Kline, Kimberly (Molecular Carcinogenesis, 2008)
Microarray analyses of human MDA-MB-435 breast cancer cells treated with vitamin E analog 2,5,7,8-tetramethyl-2R-(4R,8R,12-trimethyltridecyl) chroman-6-yloxy acetic acid (α-TEA) showed over 400 genes to be modulated. Thirty-four genes deemed of interest based on potential involvement in anticancer activities of α-TEA fell into six categories: apoptosis related, signal transduction, cell cycle related, cell adhesion and motility, transcriptional regulators, and membrane traffic related. The gene (PMAIP1) for NOXA was studied further. NOXA mRNA and protein levels were elevated in a time and dose-dependent fashion following α-TEA treatment. Functional knockdowns using small interfering RNA (siRNA) showed NOXA to contribute to α-TEA-induced apoptosis. A correlation between α-TEA's ability to upregulate NOXA and induce apoptosis was seen among several human breast cancer cell lines. Efforts to identify upstream regulators of NOXA in α-TEA-induced apoptosis identified the necessity of both c-Jun N-terminal kinase (JNK) activation and p73 expression. Additionally, protein levels of full length p73 were decreased by JNK siRNA treatment, suggesting that the signal transduction module of JNK-p73-NOXA is involved in α-TEA induced apoptosis of human breast cancer cells. Taken together, these findings suggest a role for JNK activation in mediating full length p73 expression and add to our understanding of the mechanisms of anticancer actions of α-TEA, a potential chemotherapeutic agent. © 2007 Wiley-Liss, Inc.
Keywords: DNA array; siRNA knockdown; vitamin E analog α-TEA

Involvement of the limbic basal ganglia in ethanol withdrawal convulsivity in mice is influenced by a chromosome 4 locus - Chen, Gang; Kozell, Laura B.; Hitzemann, Robert; Buck, Kari J. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2008)
Physiological dependence and associated withdrawal episodes are thought to constitute a motivational force that sustains ethanol (alcohol) use/abuse and may contribute to relapse in alcoholics. Although no animal model duplicates alcoholism, models for specific factors, like the withdrawal syndrome, are useful for identifying potential genetic and neural determinants of liability in humans. We generated congenic mice that confirm a quantitative trait locus (QTL) on chromosome 4 with a large effect on predisposition to alcohol withdrawal. Using c-Fos expression as a high-resolution marker of neuronal activation, congenic mice demonstrated significantly less neuronal activity associated with ethanol withdrawal than background strain mice in the substantia nigra pars reticulata (SNr), subthalamic nucleus (STN), rostromedial lateral globus pallidus, and ventral pallidum. Notably, neuronal activation in subregions of the basal ganglia associated with limbic function was more intense than in subregions associated with sensorimotor function. Bilateral lesions of caudolateral SNr attenuated withdrawal severity after acute and repeated ethanol exposures, whereas rostrolateral SNr and STN lesions did not reduce ethanol withdrawal severity. Caudolateral SNr lesions did not affect pentylenetetrazol-enhanced convulsions. Our results suggest that this QTL impacts ethanol withdrawal via basal ganglia circuitry associated with limbic function and that the caudolateral SNr plays a critical role. These are the first analyses to elucidate circuitry by which a confirmed addiction-relevant QTL influences behavior. This mouse QTL is syntenic with human chromosome 9p. Given the growing body of evidence that a gene(s) on chromosome 9p influences alcoholism, our results can facilitate human research on alcohol dependence and withdrawal.
Keywords: Alcohol Withdrawal Seizures; Analysis of Variance; Animal; Animals; Basal Ganglia; Biological; Chromosomes; Congenic; Disease Models; Electrolysis; Ethanol; Gene Expression Regulation; Human; Humans; Mice; Models; Nonparametric; Pair 4; Pentylenetetrazole; Proto-Oncogene Proteins c-fos; Quantitative Trait Loci; Statistics

Label-Free Comparative Analysis of Proteomics Mixtures Using Chromatographic Alignment of High-Resolution μLC−MS Data - Finney, Gregory L.; Blackler, Adele R.; Hoopmann, Michael R.; Canterbury, Jesse D.; Wu, Christine C.; MacCoss, Michael J. (Analytical Chemistry, 2008)
Label-free relative quantitative proteomics is a powerful tool for the survey of protein level changes between two biological samples. We have developed and applied an algorithm using chromatographic alignment of μLC−MS runs to improve the detection of differences between complex protein mixtures. We demonstrate the performance of our software by finding differences in E. coli protein abundance upon induction of the lac operon genes using isopropyl β-d-thiogalactopyranoside. The use of our alignment gave a 4-fold decrease in mean relative retention time error and a 6-fold increase in the number of statistically significant differences between samples. Using a conservative threshold, we have identified 5290 total μLC−MS regions that have a different abundance between these samples. Of the detected difference regions, only 23% were mapped to MS/MS peptide identifications. We detected 74 proteins that had a greater relative abundance in the induced sample and 21 with a greater abundance in the uninduced sample. We have developed an effective tool for the label-free detection of differences between samples and demonstrate an increased sensitivity following chromatographic alignment.

Lesions of the extended amygdala in C57BL/6J mice do not block the intermittent ethanol vapor-induced increase in ethanol consumption - Dhaher, Ronnie; Finn, Deborah; Snelling, Christopher; Hitzemann, Robert (Alcoholism, Clinical and Experimental Research, 2008)
BACKGROUND: The central extended amygdala (cEA) which includes the central nucleus of the amygdala (CeA) and the lateral posterior bed nucleus of the stria terminalis (BNSTLP), has been proposed to play a key role in excessive ethanol consumption in humans (Koob and Le Moal, 2005 Nat Neurosci 8:1442). To examine this relationship, we used a murine model of ethanol dependence (Becker and Lopez, 2004 Alcohol Clin Exp Res 28:1829; Lopez and Becker, 2005 Psychopharmacology (Berl) 181:688) and compared animals with sham lesions and electrolytic lesions of the CeA and BNSTLP. METHODS: Male C57BL/6J (B6) mice were first acclimated to a limited-access 2-bottle-choice preference procedure. The access period began 3 hours into the dark phase of the light-dark cycle and continued for 2 hours. Once acclimated (1 week), mice underwent chronic exposure to and intermittent withdrawal from ethanol vapor. The animals were then retested in the limited-access 2-bottle-choice preference procedure. In some experiments, electrolytic and sham lesions of the CeA or BNSTLP were performed prior to initiating the 2-bottle choice procedure. RESULTS: In a series of 5 preliminary experiments, mice were randomly assigned either to the standard intermittent ethanol vapor procedure or to the standard procedure but with air in the vapor chamber (control). The air-control procedure produced no change in ethanol intake when compared to baseline consumption. In contrast, intermittent ethanol vapor exposure increased ethanol consumption by almost 50%. The increase in consumption was associated with an increase in total fluid volume consumed and no change in ethanol preference. Lesions of both the BNSTLP and CeA significantly decreased baseline ethanol consumption, the former by decreasing fluid consumption and the latter by decreasing ethanol preference. Intermittent ethanol vapor exposure significantly increased consumption in both the BNSTLP- and CeA-lesioned animals, largely by increasing the total volume of fluid consumed. CONCLUSIONS: The results obtained clearly demonstrate that the cEA has a role in the regulation of ethanol consumption in the limited-access procedure. However, neither lesions of the CeA nor BNSTLP prevented the intermittent ethanol vapor-induced increase in consumption. These data do not preclude some role of the cEA in the increased ethanol consumption following intermittent ethanol vapor exposure, but would suggest that other brain regions also must have a significant influence.
Keywords: Administration; Alcohol Drinking; alcoholism; Amygdala; Animals; Brain Mapping; Choice Behavior; Ethanol; Inbred C57BL; Inhalation; Male; Mice; Septal Nuclei; Substance Withdrawal Syndrome

Magnetic Resonance Imaging of the Living Brain - Rosenbloom, Margaret J.; Pfefferbaum, Adolf (Alcohol Research & Health, 2008)
Magnetic resonance imaging (MRI) provides a safe, noninvasive method to examine the brain’s macrostructure, microstructure, and some aspects of how the living brain functions. MRI is capable of detecting abnormalities that can occur with alcoholism as well as changes that can occur with sobriety and relapse. The brain pathology associated with chronic excessive alcohol consumption is well documented with imaging of the living body (i.e., in vivo imaging). Consistent findings include shrinkage of the frontal cortex,1 underlying white matter, and cerebellum and expansion of the ventricles. Some of these changes are reversible with abstinence, but some appear to be enduring. Research showing correlations between brain structure and quantitative neuropsychological testing demonstrates the functional consequences of the pathology. In addition, functional imaging studies provide evidence that the brain compensates for cognitive deficits. The myriad concomitants of alcoholism, the antecedents, and the consumption patterns each may influence the observed brain changes associated with alcoholism, which tend to be more deleterious with increasing age. The multifaceted nature of alcoholism presents unique challenges and opportunities to understand the mechanisms underlying alcoholism-induced neuropathology and its recovery. Longitudinal MRI studies of animal models of alcoholism, however, can address questions about the development and course of alcohol dependence and the scope and limits of in vivo degeneration and recovery of brain structure and concomitant function that may not be readily addressed in clinical studies.

Metabotropic glutamate receptor 5 (mGluR5) regulation of ethanol sedation, dependence and consumption: relationship to acamprosate actions - Blednov, Yuri A.; Harris, R. Adron (The International Journal of Neuropsychopharmacology, 2008)
Recent studies have demonstrated that metabotropic glutamate receptor 5 (mGluR5) antagonists decrease alcohol self-administration and suggest that the anti-craving medication, acamprosate, may also act to decrease mGluR5 function. To address the role of mGluR5 in behavioural actions of ethanol and acamprosate, we compared mutant mice with deletion of the mGluR5 gene and mice treated with a mGluR5 antagonist (MPEP) or acamprosate. Lack of mGluR5 or administration of MPEP reduced the severity of alcohol-induced withdrawal (AW), increased the sedative effect of alcohol (duration of loss of righting reflex; LORR), and increased basal motor activity. The motor stimulation produced by ethanol was blocked by deletion of mGluR5, but not by injection of MPEP. Both acamprosate and MPEP increased ethanol-induced LORR and reduced AW. Importantly, the protective effects of both MPEP and acamprosate on AW were found when the drugs were injected before, but not after, injection of ethanol. This indicates that the drugs prevented development of dependence rather than merely producing an anticonvulsant action. No effects of acamprosate or MPEP on ethanol-induced LORR and AW were found in mGluR5 knockout mice, demonstrating that mGluR5 is required for these actions. mGluR5 null mutant mice showed decreased alcohol consumption in some, but not all, tests. These data show the importance of mGluR5 for several actions of alcohol and support the hypothesis that some effects of acamprosate require mGluR5 signalling.
Keywords: Alcohol Deterrents; Alcohol Drinking; alcoholism; Analysis of Variance; Animal; Animals; Behavior; Central Nervous System Depressants; Choice Behavior; Conditioning; Dose-Response Relationship; Drug; Drug Interactions; Ethanol; Excitatory Amino Acid Antagonists; Female; Inbred C57BL; Knockout; Male; Metabotropic Glutamate; Metabotropic Glutamate 5; Mice; Motor Activity; Operant; Pyridines; Receptor; Receptors; Reflex; Self Administration; Sex Factors; Taurine

Mu-opioid receptor activation induces transcriptional plasticity in the central extended amygdala - Befort, K.; Filliol, D.; Ghate, A.; Darcq, E.; Matifas, A.; Muller, J.; Lardenois, A.; Thibault, C.; Dembele, D.; Le Merrer, J.; Becker, J. a. J.; Poch, O.; et al. (The European Journal of Neuroscience, 2008)
Addiction develops from the gradual adaptation of the brain to chronic drug exposure, and involves genetic reprogramming of neuronal function. The central extended amygdala (EAc) is a network formed by the central amygdala and the bed nucleus of the stria terminalis. This key site controls drug craving and seeking behaviors, and has not been investigated at the gene regulation level. We used Affymetrix microarrays to analyze transcriptional activity in the murine EAc, with a focus on mu-opioid receptor-associated events because these receptors mediate drug reward and dependence. We identified 132 genes whose expression is regulated by a chronic escalating morphine regimen in the EAc from wild-type but not mu-opioid receptor knockout mice. These modifications are mostly EAc-specific. Gene ontology analysis reveals an overrepresentation of neurogenesis, cell growth and signaling protein categories. A separate quantitative PCR analysis of genes in the last of these groups confirms the dysregulation of both orphan (Gpr88) and known (DrD1A, Adora2A, Cnr1, Grm5, Gpr6) G protein-coupled receptors, scaffolding (PSD95, Homer1) and signaling (Sgk, Cap1) proteins, and neuropeptides (CCK, galanin). These transcriptional modifications do not occur following a single morphine injection, and hence result from long-term adaptation to excessive mu receptor activation. Proteins encoded by these genes are classically associated with spine modules function in other brain areas, and therefore our data suggest a remodeling of EAc circuits at sites where glutamatergic and monoaminergic afferences interact. Together, mu receptor-dependent genes identified in this study potentially contribute to drug-induced neural plasticity, and provide a unique molecular repertoire towards understanding drug craving and relapse.
Keywords: Amygdala; Analgesics; Animals; G-Protein-Coupled; Gene Expression Regulation; Inbred C57BL; Knockout; Male; Messenger; Mice; Morphine; mu; Neural Pathways; Neuronal Plasticity; Oligonucleotide Array Sequence Analysis; Opioid; Opioid-Related Disorders; Receptors; RNA; Septal Nuclei; Signal Transduction; Transcriptional Activation

Neuroinflammation as a neurotoxic mechanism in alcoholism: commentary on "Increased MCP-1 and microglia in various regions of human alcoholic brain" - Sullivan, Edith V.; Zahr, Natalie M. (Experimental Neurology, 2008)
Keywords: Alcohol-Induced Disorders; Brain; Central Nervous System Depressants; Chemokine CCL2; Encephalitis; Ethanol; Gliosis; Microglia; Nerve Degeneration; Nervous System

Perception of sweet taste is important for voluntary alcohol consumption in mice - Blednov, Y. A.; Walker, D.; Martinez, M.; Levine, M.; Damak, S.; Margolskee, R. F. (Genes, Brain, and Behavior, 2008)
To directly evaluate the association between taste perception and alcohol intake, we used three different mutant mice, each lacking a gene expressed in taste buds and critical to taste transduction: alpha-gustducin (Gnat3), Tas1r3 or Trpm5. Null mutant mice lacking any of these three genes showed lower preference score for alcohol and consumed less alcohol in a two-bottle choice test, as compared with wild-type littermates. These null mice also showed lower preference score for saccharin solutions than did wild-type littermates. In contrast, avoidance of quinine solutions was less in Gnat3 or Trpm5 knockout mice than in wild-type mice, whereas Tas1r3 null mice were not different from wild type in their response to quinine solutions. There were no differences in null vs. wild-type mice in their consumption of sodium chloride solutions. To determine the cause for reduction of ethanol intake, we studied other ethanol-induced behaviors known to be related to alcohol consumption. There were no differences between null and wild-type mice in ethanol-induced loss of righting reflex, severity of acute ethanol withdrawal or conditioned place preference for ethanol. Weaker conditioned taste aversion (CTA) to alcohol in null mice may have been caused by weaker rewarding value of the conditioned stimulus (saccharin). When saccharin was replaced by sodium chloride, no differences in CTA to alcohol between knockout and wild-type mice were seen. Thus, deletion of any one of three different genes involved in detection of sweet taste leads to a substantial reduction of alcohol intake without any changes in pharmacological actions of ethanol.
Keywords: Alcohol Drinking; Animals; Avoidance Learning; Classical; Conditioning; Crosses; Female; G-Protein-Coupled; Genetic; Heterotrimeric GTP-Binding Proteins; Inbred C57BL; Knockout; Male; Mice; Mutant Strains; Quinine; Receptors; Saccharin; Taste; TRPM Cation Channels

Pharmacogenetic treatments for drug addiction: alcohol and opiates - Haile, Colin N.; Kosten, Therese A.; Kosten, Thomas R. (The American Journal of Drug and Alcohol Abuse, 2008)
AIMS: Psychiatric pharmacogenetics involves the use of genetic tests that can predict the effectiveness of treatments for individual patients with mental illness such as drug dependence. This review aims to cover these developments in the pharmacotherapy of alcohol and opiates, two addictive drugs for which we have the majority of our FDA approved pharmacotherapies. METHODS: We conducted a literature review using Medline searching terms related to these two drugs and their pharmacotherapies crossed with related genetic studies. RESULTS: Alcohol's physiological and subjective effects are associated with enhanced beta-endorphin release. Naltrexone increases baseline beta-endorphin release blocking further release by alcohol. Naltrexone's action as an alcohol pharmacotherapy is facilitated by a putative functional single nucleotide polymorphism (SNP) in the opioid mu receptor gene (Al18G) which alters receptor function. Patients with this SNP have significantly lower relapse rates to alcoholism when treated with naltrexone. Caucasians with various forms of the CYP2D6 enzyme results in a 'poor metabolizer' phenotype and appear to be protected from developing opioid dependence. Others with a "ultra-rapid metabolizer" phenotype do poorly on methadone maintenance and have frequent withdrawal symptoms. These patients can do well using buprenorphine because it is not significantly metabolized by CYP2D6. CONCLUSIONS: Pharmacogenetics has great potential for improving treatment outcome as we identify gene variants that affect pharmacodynamic and pharmacokinetic factors. These mutations guide pharmacotherapeutic agent choice for optimum treatment of alcohol and opiate abuse and subsequent relapse.
Keywords: alcoholism; beta-Endorphin; Buprenorphine; Cytochrome P-450 CYP2D6; Humans; mu; Naltrexone; Narcotic Antagonists; Opioid; Opioid-Related Disorders; Polymorphism; Predictive Value of Tests; Receptors; Single Nucleotide

Protein kinase C epsilon mediation of CRF- and ethanol-induced GABA release in central amygdala - Bajo, Michal; Cruz, Maureen T.; Siggins, George R.; Messing, Robert; Roberto, Marisa (Proceedings of the National Academy of Sciences of the United States of America, 2008)
In the central amygdala (CeA), ethanol acts via corticotrophin-releasing factor (CRF) type 1 receptors to enhance GABA release. Amygdala CRF mediates anxiety associated with stress and drug dependence, and it regulates ethanol intake. Because mutant mice that lack PKCepsilon exhibit reduced anxiety-like behavior and alcohol consumption, we investigated whether PKCepsilon lies downstream of CRF(1) receptors in the CeA. Compared with PKCepsilon(+/+) CeA neurons, PKCepsilon(-/-) neurons showed increased GABAergic tone due to enhanced GABA release. CRF and ethanol stimulated GABA release in the PKCepsilon(+/+) CeA, but not in the PKCepsilon(-/-) CeA. A PKCepsilon-specific inhibitor blocked both CRF- and ethanol-induced GABA release in the PKCepsilon(+/+) CeA, confirming findings in the PKCepsilon(-/-) CeA. These results identify a PKCepsilon signaling pathway in the CeA that is activated by CRF(1) receptor stimulation, mediates GABA release at nerve terminals, and regulates anxiety and alcohol consumption.
Keywords: Alcohol Drinking; Amygdala; Animals; Anxiety; Corticotropin-Releasing Hormone; Ethanol; gamma-Aminobutyric Acid; Male; Mice; Mutant Strains; Neurons; Protein Kinase C-epsilon; Receptors; Synaptic Transmission

Proteomic approaches for studying alcoholism and alcohol-induced organ damage - Hiller-Sturmhöfel, Susanne; Sobin, Josip; Mayfield, R. Dayne (Alcohol Research & Health: The Journal of the National Institute on Alcohol Abuse and Alcoholism, 2008)
Proteomics research is concerned with the analysis of all proteins found in an organism, tissue, cell type, or cellular structure. The shotgun proteomic approach, which involves two-dimensional gel electrophoresis or liquid chromatography combined with mass spectrometry (MS), is used to identify novel proteins affected by alcohol. More targeted analyses study protein-protein interactions using such techniques as the yeast two-hybrid system, affinity chromatography, or immunoprecipitation. Finally, proteomic strategies can be combined with genomic research findings using computer analyses (i.e., in silico). All of these approaches have been used in the alcohol field. These studies have identified proteins in various brain regions whose expression is affected by alcohol. Other investigators have used proteomic approaches to identify proteins that could serve as potential biomarkers of alcohol use. Finally, interaction proteomic analyses have begun to identify proteins involved in several nerve signaling networks in the brain, which then can serve as targets for further studies on alcohol's effects. Future proteomic studies likely will shed more light on the mechanisms underlying alcohol's actions on the body.
Keywords: Alcohol Drinking; alcoholism; Animals; Brain; Humans; Mass Spectrometry; Proteomics

Quantitative chiral analysis of salsolinol in different brain regions of rats genetically predisposed to alcoholism - Rojkovicova, Tatiana; Mechref, Yehia; Starkey, Jason A.; Wu, Guangxiang; Bell, Richard L.; McBride, William J.; Novotny, Milos V. (Journal of Chromatography. B, Analytical Technologies in the Biomedical and Life Sciences, 2008)
A method to determine the catecholamine content in putamen (CPU) and midbrain (MB) regions of the brain of alcohol-preferring rats (P) is presented with a focus on the low-level detection of S,R-salsolinol, a metabolite of dopamine and a putative alcoholism marker. The developed strategy allows both quantitative profiling of related catecholamines and the enantiomeric separation and quantification of the S- and R-salsolinol isomers and their ratios. The described LC/MS strategy simplifies the current methodology that typically employs GC-MS by eliminating the need for derivatization. The data also suggest an increase in the non-enzymatic formation of salsolinol as a consequence of ethanol exposure.
Keywords: alcoholism; Animals; Brain Chemistry; Cellulose; Chromatography; Cyclodextrins; dopamine; Genetic Predisposition to Disease; Inbred Strains; Isoquinolines; Liquid; Male; Mass Spectrometry; Mesencephalon; Molecular Structure; Putamen; Rats; Reproducibility of Results; Sensitivity and Specificity; Stereoisomerism

REINSTATEMENT OF ETHANOL AND SUCROSE SEEKING BY THE NEUROSTEROID ALLOPREGNANOLONE IN C57BL/6 MICE - Finn, Deborah A.; Mark, Gregory P.; Fretwell, Andrea M.; Gililland, Katherine R.; Strong, Moriah N.; Ford, Matthew M. (Psychopharmacology, 2008)
Rationale Recent work in our laboratory documented that the “sipper” method of operant ethanol self-administration produced high ethanol intake and blood ethanol concentrations as well as the typical extinction “burst” in responding under non-reinforced conditions in male C57BL/6 mice. However, the neurochemical basis for reinstatement of responding following extinction has not been examined in mice with this model. Objectives Based on findings that the GABAergic neurosteroid allopregnanolone (ALLO) significantly increased the consummatory phase of ethanol self-administration, the present study determined the effect of ALLO on reinstatement of extinguished ethanol-seeking behavior and compared this effect to reinstatement of responding for sucrose reward. Methods Separate groups of male C57BL/6 mice were trained to lever press for access to a 10% ethanol (10E) or a 5% sucrose (5S) solution. A single response requirement of 16 presses (RR16) on an active lever resulted in 30 min of continuous access to the 10E or 5S solution. After the animals responded on the RR16 schedule for 14 weeks, mice were exposed to 30 min extinction sessions where responding had no scheduled consequence. Once responding stabilized below the pre-extinction baseline, mice received an IP injection of ALLO (0, 3.2, 5.6, 10 or 17 mg/kg) 15 min prior to the extinction session in a within-subjects design. Results ALLO produced a dose-dependent increase in responding under non-reinforced conditions in both the 10E and 5S groups. Additional work documented the ability of a conditioned cue light or a compound cue (light+lever retraction) to reinstate non-reinforced responding on the previously active lever. Conclusions These findings definitively show that conditioned cues and priming with ALLO are potent stimuli for reinstating both ethanol and sucrose seeking behavior in C57BL/6 mice.

Reproducibility study of whole-brain 1H spectroscopic imaging with automated quantification - Gu, Meng; Kim, Dong-Hyun; Mayer, Dirk; Sullivan, Edith V.; Pfefferbaum, Adolf; Spielman, Daniel M. (Magnetic Resonance in Medicine, 2008)
A reproducibility study of proton MR spectroscopic imaging ((1)H-MRSI) of the human brain was conducted to evaluate the reliability of an automated 3D in vivo spectroscopic imaging acquisition and associated quantification algorithm. A PRESS-based pulse sequence was implemented using dualband spectral-spatial RF pulses designed to fully excite the singlet resonances of choline (Cho), creatine (Cre), and N-acetyl aspartate (NAA) while simultaneously suppressing water and lipids; 1% of the water signal was left to be used as a reference signal for robust data processing, and additional lipid suppression was obtained using adiabatic inversion recovery. Spiral k-space trajectories were used for fast spectral and spatial encoding yielding high-quality spectra from 1 cc voxels throughout the brain with a 13-min acquisition time. Data were acquired with an 8-channel phased-array coil and optimal signal-to-noise ratio (SNR) for the combined signals was achieved using a weighting based on the residual water signal. Automated quantification of the spectrum of each voxel was performed using LCModel. The complete study consisted of eight healthy adult subjects to assess intersubject variations and two subjects scanned six times each to assess intrasubject variations. The results demonstrate that reproducible whole-brain (1)H-MRSI data can be robustly obtained with the proposed methods.
Keywords: Adult; Brain; Computer-Assisted; Female; Humans; Image Processing; Magnetic Resonance Imaging; Male; Protons; Radiography; Reference Standards; Reproducibility of Results

A shotgun proteomic method for the identification of membrane-embedded proteins and peptides - Blackler, Adele R.; Speers, Anna E.; Ladinsky, Mark S.; Wu, Christine C. (Journal of Proteome Research, 2008)
Integral membrane proteins perform crucial cellular functions and are the targets for the majority of pharmaceutical agents. However, the hydrophobic nature of their membrane-embedded domains makes them difficult to work with. Here, we describe a shotgun proteomic method for the high-throughput analysis of the membrane-embedded transmembrane domains of integral membrane proteins which extends the depth of coverage of the membrane proteome.
Keywords: Cell Membrane; Electron; Endopeptidase K; HeLa Cells; Humans; Membrane Proteins; Microscopy; Peptides; Proteomics; Tandem Mass Spectrometry

Strain differences in alcohol-induced neurochemical plasticity: a role for accumbens glutamate in alcohol intake - Kapasova, Zuzana; Szumlinski, Karen K. (Alcoholism, Clinical and Experimental Research, 2008)
BACKGROUND: Repeated alcohol administration alters nucleus accumbens (NAC) basal glutamate content and sensitizes the capacity of alcohol to increase NAC extracellular glutamate levels. However, the relevance of alcohol-induced changes in NAC glutamate for alcohol drinking behavior is under-investigated. METHODS: To examine the relationship between genetic variance in alcohol consumption and alcohol-induced neuroadaptations within the NAC, in vivo microdialysis was conducted in the alcohol-preferring C57BL/6J (B6) and alcohol-avoiding DBA2/J (D2) mouse strains on injections 1 and 8 of repeated alcohol treatment (8 x 2 g/kg, IP). To confirm an active role for NAC glutamate in regulating alcohol drinking behavior, the glutamate reuptake inhibitor dl-threo-beta-benzyloxyaspartic acid (TBOA) (300 microM) and the Group 2 metabotropic glutamate autoreceptor agonist (2R,4R)-4-aminopyrrolidine-2,4-dicarboxylate (APDC) (50 microM) were infused into the NAC of B6 and D2 mice prior to alcohol consumption in a 4 bottle-choice test. RESULTS: While strain differences were not apparent for NAC basal levels of dopamine, serotonin or gamma-amino butyric acid (GABA), repeated alcohol treatment elevated NAC basal glutamate content only in B6 mice. Strain differences in both the acute and the sensitized neurochemical responses to 2 g/kg alcohol were observed for all neurotransmitters examined. While the alcohol-induced rise in NAC dopamine and glutamate levels sensitized in B6 mice, a sensitization was not observed in D2 animals. Moreover, B6 mice exhibited a sensitized serotonin and GABA response to alcohol followed repeated treatment, whereas neither tolerance nor sensitization was observed in D2 animals. An intra-NAC APDC infusion reduced alcohol intake in both B6 and D2 mice by approximately 50%. In contrast, TBOA infusion elevated alcohol intake selectively in B6 mice. CONCLUSIONS: These data indicate an active role for NAC glutamate in regulating alcohol consumption in mice and support the hypothesis that predisposition to high alcohol intake involves genetic factors that facilitate alcohol-induced adaptations in glutamate release within the NAC.
Keywords: Alcohol Drinking; Animals; Ethanol; Glutamic Acid; Inbred C57BL; Inbred DBA; Male; Mice; Microdialysis; Neuronal Plasticity; Nucleus Accumbens; Species Specificity

Stress-dependent dynamics of global chromatin remodeling in yeast: dual role for SWI/SNF in the heat shock stress response - Shivaswamy, Sushma; Iyer, Vishwanath R. (Molecular and Cellular Biology, 2008)
Although chromatin structure is known to affect transcriptional activity, it is not clear how broadly patterns of changes in histone modifications and nucleosome occupancy affect the dynamic regulation of transcription in response to perturbations. The identity and role of chromatin remodelers that mediate some of these changes are also unclear. Here, we performed temporal genome-wide analyses of gene expression, nucleosome occupancy, and histone H4 acetylation during the response of yeast (Saccharomyces cerevisiae) to different stresses and report several findings. First, a large class of predominantly ribosomal protein genes, whose transcription was repressed during both heat shock and stationary phase, showed strikingly contrasting histone acetylation patterns. Second, the SWI/SNF complex was required for normal activation as well as repression of genes during heat shock, and loss of SWI/SNF delayed chromatin remodeling at the promoters of activated genes. Third, Snf2 was recruited to ribosomal protein genes and Hsf1 target genes, and its occupancy of this large set of genes was altered during heat shock. Our results suggest a broad and direct dual role for SWI/SNF in chromatin remodeling, during heat shock activation as well as repression, at promoters and coding regions.
Keywords: Adenosine Triphosphatases; Chromatin Assembly and Disassembly; Chromatin Immunoprecipitation; DNA-Binding Proteins; Fungal; Gene Expression Regulation; Genetic; Heat-Shock Proteins; Histones; Hot Temperature; Models; Nucleosomes; Oligonucleotide Array Sequence Analysis; Promoter Regions; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins; Transcription; Transcription Factors

Targeting Homer genes using adeno-associated viral vector: lessons learned from behavioural and neurochemical studies - Klugmann, Matthias; Szumlinski, Karen K. (Behavioural Pharmacology, 2008)
Over a decade of in-vitro data support a critical role for members of the Homer family of postsynaptic scaffolding proteins in regulating the functional architecture of glutamate synapses. Earlier studies of Homer knockout mice indicated a necessary role for Homer gene products in normal mesocorticolimbic glutamate transmission and behaviours associated therewith. The advent of adeno-associated viral vectors carrying cDNA for, or short hairpin RNA against, specific Homer isoforms enabled the site-directed targeting of Homers to neurons in the brain. This approach has allowed our groups to address developmental issues associated with conventional knockout mice, to confirm active roles for distinct Homer isoforms in regulating glutamate transmission in vivo, as well as in mediating a variety of behavioural processes. This review summarizes the existing data derived from our studies using adeno-associated viral vector-mediated neuronal targeting of Homer in rodents, implicating this family of proteins in drug and alcohol addiction, learning/memory and emotional processing.
Keywords: addiction; adeno-associated viral vector; Anxiety; glutamate; Hippocampus; Homer proteins; Knockout; Memory; Mouse; Nucleus Accumbens; RNA Interference

Transcriptome analysis identifies genes with enriched expression in the mouse central Extended Amygdala - Becker, Jérôme A. J.; Befort, Katia; Blad, Clara; Filliol, Dominique; Ghate, Aditee; Dembele, Doulaye; Thibault, Christelle; Koch, Muriel; Muller, Jean; Lardenois, Aurélie; Poch, Olivier; Kieffer, Brigitte L. (Neuroscience, 2008)
The central Extended Amygdala (EAc) is an ensemble of highly interconnected limbic structures of the anterior brain, and forms a cellular continuum including the Bed Nucleus of the Stria Terminalis (BNST), the central nucleus of the Amygdala (CeA) and the Nucleus Accumbens shell (AcbSh). This neural network is a key site for interactions between brain reward and stress systems, and has been implicated in several aspects of drug abuse. In order to increase our understanding of EAc function at the molecular level, we undertook a genome-wide screen (Affymetrix) to identify genes whose expression is enriched in the EAc. We focused on the less-well known BNST-CeA areas of the EAc, and identified 121 genes that exhibit more than 2-fold higher expression level in the EAc compared to whole brain. Among these, forty-three genes have never been described to be expressed in the EAc. We mapped these genes throughout the brain, using non-radioactive in situ hybridization, and identified eight genes with a unique and distinct rostro-caudal expression pattern along AcbSh, BNST and CeA. Q-PCR analysis performed in brain and peripheral organ tissues indicated that, with the exception of one (Spata13), all these genes are predominantly expressed in brain. These genes encode signaling proteins (Adora2, GPR88, Arpp21 and Rem2), a transcription factor (Limh6) or proteins of unknown function (Rik130, Spata13 and Wfs1). The identification of genes with enriched expression expands our knowledge of EAc at a molecular level, and provides useful information to towards genetic manipulations within the EAc.

Translational studies of alcoholism: bridging the gap - Zahr, Natalie M.; Sullivan, Edith V. (Alcohol Research & Health: The Journal of the National Institute on Alcohol Abuse and Alcoholism, 2008)
Human studies are necessary to identify and classify the brain systems predisposing individuals to develop alcohol use disorders and those modified by alcohol, while animal models of alcoholism are essential for a mechanistic understanding of how chronic voluntary alcohol consumption becomes compulsive, how brain systems become damaged, and how damage resolves. Our current knowledge of the neuroscience of alcohol dependence has evolved from the interchange of information gathered from both human alcoholics and animal models of alcoholism. Together, studies in humans and animal models have provided support for the involvement of specific brain structures over the course of alcohol addiction, including the prefrontal cortex, basal ganglia, cerebellum, amygdala, hippocampus, and the hypothalamic-pituitary-adrenal axis.
Keywords: alcohol and other drug effects and consequences; Alcohol dependence; Alcohol Drinking; alcoholism; Animal; animal models; animal studies; Animals; Brain; chronic alcohol exposure; Disease Models; environmental factors; Ethanol; genetic factors; human studies; Humans; Nerve Net; neurobiology; Translational Medical Research; translational studies

Urocortin 1 microinjection into the mouse lateral septum regulates the acquisition and expression of alcohol consumption - Ryabinin, A. E.; Yoneyama, N.; Tanchuck, M. A.; Mark, G. P.; Finn, D. A. (Neuroscience, 2008)
Previous studies using genetic and lesion approaches have shown that the neuropeptide urocortin 1 (Ucn1) is involved in regulating alcohol consumption. Ucn1 is a corticotropin releasing factor (CRF) -like peptide that binds CRF1 and CRF2 receptors. Perioculomotor urocortin-containing neurons (pIIIu), also known as the non-preganglionic Edinger-Westphal nucleus, are the major source of Ucn1 in the brain and are known to innervate the lateral septum. Thus, the present study tested whether Ucn1 could regulate alcohol consumption through the lateral septum. In a series of experiments Ucn1 or CRF was bilaterally injected at various doses into the lateral septum of male C57BL/6J mice. Consumption of 20% volume/volume ethanol or water was tested immediately after the injections using a modification of a 2-h limited access sweetener-free "drinking-in-the-dark" procedure. Ucn1 significantly suppressed ethanol consumption when administered prior to the third ethanol drinking session (the expression phase of ethanol drinking) at doses as low as 6 pmol. Ethanol intake was differentially sensitive to Ucn1, as equivalent doses of this peptide did not suppress water consumption. In contrast, CRF suppressed both ethanol and water intake at 40 and 60 pmol, but not at lower doses. Repeated administration of Ucn1 during the acquisition of alcohol consumption showed that 40 pmol (but not 2 or 0.1 pmol) significantly attenuated ethanol intake. Repeated administration of Ucn1 also resulted in a decrease of ethanol intake in sham-injected animals, a finding suggesting that the suppressive effect of Ucn1 on ethanol intake can be conditioned. Taken together, these studies confirm the importance of lateral septum innervation by Ucn1 in the regulation of alcohol consumption.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Central Nervous System Depressants; Corticotropin-Releasing Hormone; Dose-Response Relationship; Drinking; Drinking Behavior; Drug; Ethanol; Inbred C57BL; Male; Mice; Microinjections; Septal Nuclei; Time Factors; Urocortins

Using drinking in the dark to model prenatal binge-like exposure to ethanol in C57BL/6J mice - Boehm, Stephen L.; Moore, Eileen M.; Walsh, Cherie D.; Gross, Carly D.; Cavelli, Austin M.; Gigante, Eduardo; Linsenbardt, David N. (Developmental Psychobiology, 2008)
Animal models of prenatal ethanol exposure are necessary to more fully understand the effects of ethanol on the developing embryo/fetus. However, most models employ procedures that may produce additional maternal stress beyond that produced by ethanol alone. We employed a daily limited-access ethanol intake model called Drinking in the Dark (DID) to assess the effects of voluntary maternal binge-like ethanol intake on the developing mouse. Evidence suggests that binge exposure may be particularly harmful to the embryo/fetus, perhaps due to the relatively higher blood ethanol concentrations achieved. Pregnant females had mean daily ethanol intakes ranging from 4.2 to 6.4 g/kg ethanol over gestation, producing blood ethanol concentrations ranging from 115 to 182 mg/dL. This level of ethanol intake produced behavioral alterations among adolescent offspring that disappeared by adulthood, including altered sensitivity to ethanol's hypnotic actions. The DID model may provide a useful tool for studying the effects of prenatal ethanol exposure in mice.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Anxiety; Behavior; Body Weight; Circadian Rhythm; Darkness; Disease Models; Eating; Ethanol; Female; Inbred C57BL; Male; Maternal Behavior; Mice; Motor Activity; Pregnancy; Prenatal Exposure Delayed Effects; Reflex; Sex Distribution; Water

Ventricular expansion in wild-type Wistar rats after alcohol exposure by vapor chamber - Pfefferbaum, Adolf; Zahr, Natalie M.; Mayer, Dirk; Vinco, Shara; Orduna, Juan; Rohlfing, Torsten; Sullivan, Edith V. (Alcoholism, Clinical and Experimental Research, 2008)
BACKGROUND: Structural magnetic resonance imaging (MRI) reveals widespread brain damage manifest as tissue shrinkage and complementary ventriculomegaly in human alcoholism. For an animal model to parallel the human condition, high alcohol exposure should produce similar radiologically detectable neuropathology. Our previous structural MRI study demonstrated only modest brain dysmorphology of the alcohol-preferring (P) rat with average blood alcohol levels(BALs) of 125 mg/dl achieved with voluntary consumption. Here, we tested the hypothesis that wild-type Wistar rats, exposed to vaporized alcohol ensuring higher BALs than typically achieved with voluntary consumption in rodents, would model MRI findings in the brains of humans with chronic alcoholism. METHODS: The longitudinal effects of vaporized alcohol exposure on the brains of 10 wild-type Wistar rats compared with 10 sibling controls were investigated with structural MRI, conducted before (MRI 1) and after (MRI 2) 16 of alcohol exposure and after an additional 8 weeks at a higher concentration of alcohol (MRI 3). RESULTS: Two rats in the alcohol group died prior to MRI 2. The remaining vapor-exposed rats(n = 8) achieved BALs of 293 mg/dl by MRI 2 and 445 mg/dl by MRI 3. Whereas the controls gained 17% of their body weight from MRI 1 to MRI 3, the alcohol-exposed group lost 6%.MRI, quantified with atlas-based parcellation, revealed a profile of significant ventricular expansion,after alcohol vapor exposure, in 9 contiguous slices, extending from the dorsolateral to ventrolateral ventricles. In particular, from MRI 1 to MRI 2, this ventricular volume expanded by an average of 6.5% in the controls and by 27.1% in the alcohol-exposed rats but only an additional 1.5% in controls and 2.4% in alcohol-exposed rats from MRI 2 to MRI 3. The midsagittal volume of the full anterior-to-posterior extent of the corpus callosum grew between the first 2 MRIs in both groups followed by regression in the alcohol group by MRI 3. Although group differences were statistically significant, among animals there was substantial variability of the effects of alcohol exposure on brain morphology; some animals showed profound effects, whereas others were essentially unaffected. CONCLUSIONS: The ventricular dilatation and callosal shrinkage produced in wild-type rats following involuntary alcohol exposure yielded a modestly successful model of neurodysmorphology phenotypes of human alcoholism. As is the case for the human condition, however, in which some individuals express greater alcoholism-related neuropathology than others, some rats maybe more susceptible than others to extreme alcohol exposure.
Keywords: Administration; alcoholism; Animal; Animals; Body Weight; Central Nervous System Depressants; Cerebral Ventricles; Corpus Callosum; Disease Models; Dose-Response Relationship; Drug; Ethanol; Female; Inhalation; Magnetic Resonance Imaging; Male; Nebulizers and Vaporizers; Rats; Wistar

Voluntary ethanol consumption in 22 inbred mouse strains - Yoneyama, Naomi; Crabbe, John C.; Ford, Matthew M.; Murillo, Andrea; Finn, Deborah A. (Alcohol (Fayetteville, N.Y.), 2008)
Inbred strains are genetically stable across time and laboratories, allowing scientists to accumulate a record of phenotypes, including physiological characteristics and behaviors. To date, the C57/C58 family of inbred mouse strains has been identified as having the highest innate ethanol consumption, but some lineages have rarely or never been surveyed. Thus, the purpose of the present experiment was to measure ethanol preference and intake in 22 inbred mouse strains, some of which have never been tested for ethanol consumption. Male and female mice (A/J, BALB/cByJ, BTBR+T(tf/tf), BUB/BnJ, C57BL/6J, C57BLKS/J, C58/J, CZECH/Ei, DBA/2J, FVB/NJ, I/LnJ, LP/J, MA/MyJ, NOD/LtJ, NON/LtJ, NZB/B1NJ, NZW/LacJ, PERA/Ei, RIIIS/J, SEA/GnJ, SM/J, and 129S1/SvlmJ) were individually housed and given unlimited access in a two-bottle choice procedure to one bottle containing tap water and a second containing increasing concentrations of ethanol (3%, 6%, 10%), 0.2% saccharin, and then increasing concentrations of ethanol (3%, 6%, 10%) plus 0.2% saccharin. Mice were given access to each novel solution for a total of 4 days, with a bottle side change every other day. Consistent with previous studies, C57BL/6J (B6) mice consumed an ethanol dose of >10g/kg/day whereas DBA/2J (D2) mice consumed <2g/kg/day. No strain voluntarily consumed greater doses of ethanol than B6 mice. Although the C58 and C57BLKS strains showed high ethanol consumption levels that were comparable to B6 mice, the BUB and BTBR strains exhibited low ethanol intakes similar to D2 mice. The addition of 0.2% saccharin to the ethanol solutions significantly increased ethanol intake by most strains and altered the strain distribution pattern. Strong positive correlations (rs> or =0.83) were determined between consumption of the unsweetened versus sweetened ethanol solutions. Consumption of saccharin alone was significantly positively correlated with the sweetened ethanol solutions (rs=0.62-0.81), but the correlation with unsweetened ethanol solutions was considerably lower (rs=0.37-0.45). These results add new strains to the strain mean database that will facilitate the identification of genetic relationships between voluntary ethanol consumption, saccharin preference, and other phenotypes.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Central Nervous System Depressants; Data Interpretation; Databases; Ethanol; Genetic; Inbred Strains; Mice; Phenotype; Saccharin; Statistical; Sweetening Agents

Wheel running, voluntary ethanol consumption, and hedonic substitution - Ozburn, Angela Renee; Harris, R. Adron; Blednov, Yuri A. (Alcohol (Fayetteville, N.Y.), 2008)
Few studies have examined the relationship between naturally rewarding behaviors and ethanol drinking behaviors in mice. Although natural and drug reinforcers activate similar brain circuitry, there is behavioral evidence suggesting food and drug rewards differ in perceived value. The primary goal of the present study was to investigate the relationships between naturally reinforcing stimuli and consumption of ethanol in ethanol preferring C57BL/6J mice. Mouse behaviors were observed after the following environmental manipulations: standard or enhanced environment, accessible or inaccessible wheel, and presence or absence of ethanol. Using a high-resolution volumetric drinking monitor and wheel running monitor, we evaluated whether alternating access to wheel running modified ethanol-related behaviors and whether alternating access to ethanol modified wheel running or subsequent ethanol-related behaviors. We found that ethanol consumption remains stable with alternating periods of wheel running. Wheel running increases in the absence of ethanol and decreases upon reintroduction of ethanol. Upon reintroduction of ethanol, an alcohol deprivation effect was seen. Collectively, the results support theories of hedonic substitution and suggest that female C57BL/6J mice express ethanol seeking and craving under these specific conditions.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Ethanol; Female; Inbred C57BL; Mice; Physical Exertion; Reinforcement (Psychology); Reward; Running; Self Administration; Time Factors; Volition

Aberrant synaptic activation of N-methyl-D-aspartate receptors underlies ethanol withdrawal hyperexcitability - Hendricson, Adam W.; Maldve, Regina E.; Salinas, Armando G.; Theile, Jonathan W.; Zhang, Tao A.; Diaz, Laurea M.; Morrisett, Richard A. (The Journal of Pharmacology and Experimental Therapeutics, 2007)
Chronic ethanol exposure may induce neuroadaptive responses in N-methyl-d-aspartate (NMDA) receptors, which are thought to underlie a variety of alcohol-related brain disorders. Here, we demonstrate that hyperexcitability triggered by withdrawal from chronic ethanol exposure is associated with increases in both synaptic NMDA receptor expression and activation. Withdrawal from chronic ethanol exposure (75 mM ethanol, 5-9 days) elicited robust and prolonged epileptiform activity in CA1 pyramidal neurons from hippocampal explants, which was absolutely dependent upon NMDA receptor activation but independent of chronic inhibition of protein kinase A (PKA). Analysis of Sr(2+)-supported asynchronous NMDA receptor-mediated miniature excitatory postsynaptic currents (mEPSCs) was employed to assess changes in NMDA neurotransmission. After chronic exposure, ethanol withdrawal was associated with an increase in mEPSC amplitude 3.38-fold over that after withdrawal from acute ethanol exposure. Analysis of paired evoked alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid EPSCs and spontaneous mEPSCs indicated that withdrawal after chronic exposure was also associated with a selective increase in action potential evoked but not spontaneous transmitter release probability. Immunoblot analysis revealed significant increases in total NR1, NR2A, and NR2B subunit expression after chronic exposure and unaffected by PKA-inhibition manner. Confocal imaging studies indicate that increased NR1 subunit expression was associated with increased density of NR1 expression on dendrites in parallel with a selective increase in the size of NR1 puncta on dendritic spines. Therefore, neuroadaptation to chronic ethanol exposure in NMDA synaptic transmission is responsible for aberrant network excitability after withdrawal and results from changes in both postsynaptic function as well as presynaptic release.
Keywords: alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; Animals; Blotting; Central Nervous System Depressants; Computer-Assisted; Confocal; Cyclic AMP-Dependent Protein Kinases; Electrochemistry; Electrophysiology; Ethanol; Excitatory Amino Acid Agonists; Excitatory Postsynaptic Potentials; Female; Green Fluorescent Proteins; Hippocampus; Hyperkinesis; Image Processing; Immunohistochemistry; Male; Microscopy; Motor Endplate; N-Methyl-D-Aspartate; Organ Culture Techniques; Patch-Clamp Techniques; Rats; Receptors; Seizures; Sprague-Dawley; Substance Withdrawal Syndrome; Synapses; Synaptic Transmission; Western

Accumbens neurochemical adaptations produced by binge-like alcohol consumption - Szumlinski, Karen K.; Diab, Mahdi E.; Friedman, Raquel; Henze, Liezl M.; Lominac, Kevin D.; Bowers, M. Scott (Psychopharmacology, 2007)
RATIONALE: The Scheduled High Alcohol Consumption (SHAC) binge drinking model is a simple, partial murine model with which to investigate some of the neurobiological underpinnings of alcoholism. OBJECTIVES: The SHAC model was used to characterize monoamine and amino acid adaptations produced in the nucleus accumbens (NAC) by repeated bouts of high alcohol consumption. METHODS: In vivo microdialysis was conducted in the NAC of C57BL/6J (B6) mice during consumption of water, a 5% alcohol (v/v) solution for the first time (SHAC1) or a 5% alcohol solution for the sixth time (SHAC6). A second set of microdialysis experiments assessed the neurotransmitter response to an alcohol challenge injection (1.5 or 2 g/kg, IP). RESULTS: In both drinking experiments, SHAC1 and SHAC6 mice consumed comparable amounts of alcohol during the 40-min period of alcohol availability (approximately 1.5 g/kg) and total fluid intake was similar between water and SHAC1/6 mice. Despite the similarity in alcohol consumption, alcohol-mediated increases in the extracellular concentration of GABA and serotonin were reduced, but glutamate was increased in the NAC of SHAC6 mice, relative to SHAC1 animals. No differences were observed in extracellular dopamine between SHAC1 and SHAC6 mice during alcohol consumption. After alcohol injection, SHAC6 mice also exhibited sensitized glutamate release, but did not differ from water or SHAC1 animals for any of the other neurotransmitters examined. Brain alcohol concentrations did not differ between groups after injection. CONCLUSIONS: Repeated bouts of high alcohol consumption induce an imbalance between inhibitory and excitatory neurotransmission within the NAC that may drive excessive drinking behavior.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Central Nervous System Depressants; Disease Models; dopamine; Ethanol; gamma-Aminobutyric Acid; Glutamic Acid; Inbred C57BL; Male; Mice; Microdialysis; Nucleus Accumbens; Reproducibility of Results; Serotonin; Time Factors

Acute effects of naltrexone and GBR 12909 on ethanol drinking-in-the-dark in C57BL/6J mice - Kamdar, N. K.; Miller, S. A.; Syed, Y. M.; Bhayana, R.; Gupta, T.; Rhodes, J. S. (Psychopharmacology, 2007)
RATIONALE: Recently, a simple procedure was described, drinking in the dark (DID), in which C57BL/6J mice self-administer ethanol to the point of intoxication. The test consists of replacing the water with 20% ethanol in the home cage for 2 or 4 h early during the dark phase of the light/dark cycle. OBJECTIVES: To determine whether the model displays predictive validity with naltrexone, and whether opioid or dopaminergic mechanisms mediate excessive drinking in the model. MATERIALS AND METHODS: Naltrexone or GBR 12909 were administered via intraperitoneal injections immediately before offering ethanol solutions, plain tap water, or 10% sugar water to male C57BL/6J mice, and consumption was monitored over a 2- or 4-h period using the DID procedure. RESULTS: Naltrexone (0.5, 1, or 2 mg/kg) dose dependently decreased ethanol drinking but these same doses had no significant effect on the consumption of plain water or 10% sugar water. GBR 12909 (5, 10, and 20 mg/kg) dose dependently reduced the consumption of ethanol and sugar water but had no effect on plain water drinking. CONCLUSIONS: The DID model demonstrates predictive validity. Both opioid and dopamine signaling are involved in ethanol drinking to intoxication. Different physiological pathways mediate high ethanol drinking as compared to water or sugar water drinking in DID. DID may be a useful screening tool to find new alcoholism medications and to discover genetic and neurobiological mechanisms relevant to the human disorder.
Keywords: Alcohol Drinking; Alcoholic Intoxication; Animal; Animals; Behavior; Central Nervous System Depressants; Darkness; Disease Models; Dopamine Uptake Inhibitors; Dose-Response Relationship; Drinking Behavior; Drug; Ethanol; Inbred C57BL; Injections; Intraperitoneal; Male; Mice; Naltrexone; Narcotic Antagonists; Piperazines; Reproducibility of Results; Self Administration; Signal Transduction

Advances in neuromembrane proteomics: efforts towards a comprehensive analysis of membrane proteins in the brain - Grant, Kathleen J.; Wu, Christine C. (Briefings in Functional Genomics & Proteomics, 2007)
Proteomic investigation of normal and diseased brain states has the potential to reveal novel molecular therapeutic and diagnostic targets for a multitude of pathological central nervous system conditions. Due to their unique properties, integral membrane proteins are likely to play a central role in the aetiology of these disorders. These properties, however, have prevented comprehensive analysis of this important class of proteins. Recent advances in sample preparation and proteomic quantification platforms, specifically focused on recovery and enrichment of integral membrane proteins, are discussed.
Keywords: Animals; Biological; Brain Chemistry; Cell Membrane; Electrophoresis; Gel; Humans; Membrane Proteins; Models; Neurons; Proteome; Proteomics; Specimen Handling; Staining and Labeling; Two-Dimensional

Altered gene expression profiles in the frontal cortex of cirrhotic alcoholics - Liu, Jianwen; Lewohl, Joanne M.; Harris, R. Adron; Dodd, Peter R.; Mayfield, R. Dayne (Alcoholism, Clinical and Experimental Research, 2007)
BACKGROUND: Cirrhosis is the result of chronic liver disease that causes scarring and dysfunction of the liver. The disease is a common concomitant condition resulting from sustained exposure to alcohol. Heavy alcohol use results in brain damage that is generally more severe in cirrhotic compared with noncirrhotic alcoholics. We examined, at the cellular level, gene expression in the frontal cortex of cirrhotic alcoholics. METHODS: Gene expression profiles were compared between cirrhotic and noncirrhotic alcoholics using approximately 47,000 element cDNA microarrays. RESULTS: Widespread differences in transcriptome patterns were observed in cirrhotic compared with noncirrhotic alcoholics and these differences in gene expression accurately distinguished cirrhotic from noncirrhotic alcoholics. Functionally related groups of genes were identified that are involved in cell adhesion, mitochondrial function, synaptic transmission, apoptosis, and cell proliferation. Both astrocytes and neuronal cells were affected at the transcriptional level. The regulated genes are involved in neurite growth, neuronal cell adhesion, synaptic vesicle release, and postsynaptic neurotransmission. CONCLUSIONS: These changes in the transcriptome likely contribute to the more severe brain dysfunction in cirrhotic alcoholics.
Keywords: Adult; Aged; Alcoholic; Apoptosis; Case-Control Studies; Cell Adhesion; Cell Proliferation; Female; Frontal Lobe; Gene Expression Profiling; Gene Expression Regulation; Humans; Liver Cirrhosis; Male; Middle Aged; Mitochondria; Oligonucleotide Array Sequence Analysis; Synaptic Transmission

The atypical cadherin flamingo regulates synaptogenesis and helps prevent axonal and synaptic degeneration in Drosophila - Bao, Hong; Berlanga, Monica L.; Xue, Mingshan; Hapip, Sara M.; Daniels, Richard W.; Mendenhall, John M.; Alcantara, Adriana A.; Zhang, Bing (Molecular and Cellular Neurosciences, 2007)
The formation of synaptic connections with target cells and maintenance of axons are highly regulated and crucial for neuronal function. The atypical cadherin and G-protein-coupled receptor Flamingo and its orthologs in amphibians and mammals have been shown to regulate cell polarity, dendritic and axonal growth, and neural tube closure. However, the role of Flamingo in synapse formation and function and in axonal health remains poorly understood. Here we show that fmi mutations cause a significant increase in the number of ectopic synapses on muscles and result in the formation of novel en passant synapses along axons, and unique presynaptic varicosities, including active zones, within axons. The fmi mutations also cause defective synaptic responses in a small subset of muscles, an age-dependent loss of muscle innervation and a drastic degeneration of axons in 3rd instar larvae without an apparent loss of neurons. Neuronal expression of Flamingo rescues all of these synaptic and axonal defects and larval lethality. Based on these observations, we propose that Flamingo is required in neurons for synaptic target selection, synaptogenesis, the survival of axons and synapses, and adult viability. These findings shed new light on a possible role for Flamingo in progressive neurodegenerative diseases.
Keywords: Animals; Axons; Cadherins; Central Nervous System; Computer-Assisted; Confocal; Drosophila; Drosophila Proteins; Electron; Image Processing; Immunohistochemistry; Microscopy; Mutation; Nerve Degeneration; Neuromuscular Junction; Organogenesis; Patch-Clamp Techniques; Synapses; Transmission

Candidate genes, pathways and mechanisms for alcoholism: an expanded convergent functional genomics approach - Rodd, Z. A.; Bertsch, B. A.; Strother, W. N.; Le-Niculescu, H.; Balaraman, Y.; Hayden, E.; Jerome, R. E.; Lumeng, L.; Nurnberger, J. I.; Edenberg, H. J.; McBride, W. J.; Niculescu, A. B. (The Pharmacogenomics Journal, 2007)
We describe a comprehensive translational approach for identifying candidate genes for alcoholism. The approach relies on the cross-matching of animal model brain gene expression data with human genetic linkage data, as well as human tissue data and biological roles data, an approach termed convergent functional genomics. An analysis of three animal model paradigms, based on inbred alcohol-preferring (iP) and alcohol-non-preferring (iNP) rats, and their response to treatments with alcohol, was used. A comprehensive analysis of microarray gene expression data from five key brain regions (frontal cortex, amygdala, caudate-putamen, nucleus accumbens and hippocampus) was carried out. The Bayesian-like integration of multiple independent lines of evidence, each by itself lacking sufficient discriminatory power, led to the identification of high probability candidate genes, pathways and mechanisms for alcoholism. These data reveal that alcohol has pleiotropic effects on multiple systems, which may explain the diverse neuropsychiatric and medical pathology in alcoholism. Some of the pathways identified suggest avenues for pharmacotherapy of alcoholism with existing agents, such as angiotensin-converting enzyme (ACE) inhibitors. Experiments we carried out in alcohol-preferring rats with an ACE inhibitor show a marked modulation of alcohol intake. Other pathways are new potential targets for drug development. The emergent overall picture is that physical and physiological robustness may permit alcohol-preferring individuals to withstand the aversive effects of alcohol. In conjunction with a higher reactivity to its rewarding effects, they may able to ingest enough of this nonspecific drug for a strong hedonic and addictive effect to occur.
Keywords: Alcohol Drinking; alcoholism; Angiotensin-Converting Enzyme Inhibitors; Animal; Animals; Bayes Theorem; Behavior; Brain; Central Nervous System Depressants; Cluster Analysis; Databases; Ethanol; Gene Expression Profiling; Gene Regulatory Networks; Genetic; Genetic Predisposition to Disease; Genomics; Humans; Inbred Strains; Lisinopril; Male; Oligonucleotide Array Sequence Analysis; Rats; Reproducibility of Results; Research Design; Risk Factors; Self Administration; Time Factors

Computer automated movement detection for the analysis of behavior - Ramazani, Roseanna B.; Krishnan, Harish R.; Bergeson, Susan E.; Atkinson, Nigel S. (Journal of Neuroscience Methods, 2007)
Currently, measuring ethanol behaviors in flies depends on expensive image analysis software or time intensive experimental observation. We have designed an automated system for the collection and analysis of locomotor behavior data, using the IEEE 1394 acquisition program dvgrab, the image toolkit ImageMagick and the programming language Perl. In the proposed method, flies are placed in a clear container and a computer-controlled camera takes pictures at regular intervals. Digital subtraction removes the background and non-moving flies, leaving white pixels where movement has occurred. These pixels are tallied, giving a value that corresponds to the number of animals that have moved between images. Perl scripts automate these processes, allowing compatibility with high-throughput genetic screens. Four experiments demonstrate the utility of this method, the first showing heat-induced locomotor changes, the second showing tolerance to ethanol in a climbing assay, the third showing tolerance to ethanol by scoring the recovery of individual flies, and the fourth showing a mouse's preference for a novel object. Our lab will use this method to conduct a genetic screen for ethanol-induced hyperactivity and sedation, however, it could also be used to analyze locomotor behavior of any organism.
Keywords: Alcohol Drinking; Animal; Animals; Automation; Diptera; Disease Models; Drug Tolerance; Female; Male; Motor Activity

Conditional gene targeting in the mouse nervous system: Insights into brain function and diseases - Gavériaux-Ruff, Claire; Kieffer, Brigitte L. (Pharmacology & Therapeutics, 2007)
Conditional gene knockout represents an extremely powerful approach to study the function of single genes in the nervous system. The Cre-LoxP system is the most advanced technology for spatial and temporal control of genetic inactivation, and there is rapid progress using this methodology in neuroscience research. In this approach, mice with LoxP sites flanking the gene of interest (floxed mice) are bred with transgenic mice expressing Cre recombinase under the control of a selected promoter (Cre mice). This promoter is critical in that it determines the time and site of Cre expression. Cre enzyme, in turn, recombines the floxed gene and produces gene knockout. Here we review Cre mouse lines that have been developed to target either the entire brain, selected brain areas, or specific neuronal populations. We then summarize phenotypic consequences of conditional gene targeting in the brain for more than 40 genes, as reported to date. For many broadly expressed genes, brain-restricted knockout has overcome lethality of conventional knockout (KO) and has highlighted a specific role of the encoded protein in some aspect of brain function. In the case of neural genes, data from null mutants in specific brain sites or neurons has refined our understanding of the role of individual molecules that regulate complex behaviors or synaptic plasticity within neural circuits. Among the many developing functional genomic approaches, conditional gene targeting in the mouse has become an excellent tool to elucidate the function of the approximately 5000 known or unknown genes that operate in the nervous system.
Keywords: Animal; Animals; Behavior; Brain; Brain Diseases; Gene Expression Regulation; Gene Targeting; Integrases; Knockout; Mice; Models; Nervous System; Nervous System Diseases; Phenotype; Transgenic

Defining the dopamine transporter proteome by convergent biochemical and in silico analyses - Maiya, R.; Ponomarev, I.; Linse, K. D.; Harris, R. A.; Mayfield, R. D. (Genes, Brain, and Behavior, 2007)
Monoamine transporters play a key role in neuronal signaling by mediating reuptake of neurotransmitters from the synapse. The function of the dopamine transporter (DAT), an important member of this family of transporters, is regulated by multiple signaling mechanisms, which result in altered cell surface trafficking of DAT. Protein-protein interactions are likely critical for this mode of transporter regulation. In this study, we identified proteins associated with DAT by immunoprecipitation (IP) followed by mass spectrometry. We identified 20 proteins with diverse cellular functions that can be classified as trafficking proteins, cytoskeletal proteins, ion channels and extracellular matrix-associated proteins. DAT was found to associate with the voltage-gated potassium channel Kv2.1 and synapsin Ib, a protein involved in regulating neurotransmitter release. An in silico analysis provided evidence for common transcriptional regulation of the DAT proteome genes. In summary, this study identified a network of proteins that are primary candidates for functional regulation of the DAT, an important player in mechanisms of mental disorders and drug addiction.
Keywords: Animals; Dopamine Plasma Membrane Transport Proteins; Gene Expression Regulation; Mass Spectrometry; Mice; Neostriatum; Potassium Channels; Protein Interaction Mapping; Protein Transport; Proteome; Synapsins; Synaptosomes; Voltage-Gated

Dependence-induced increases in ethanol self-administration in mice are blocked by the CRF1 receptor antagonist antalarmin and by CRF1 receptor knockout - Chu, Kathleen; Koob, George F.; Cole, Maury; Zorrilla, Eric P.; Roberts, Amanda J. (Pharmacology Biochemistry and Behavior, 2007)
Models of dependence-induced increases in ethanol self-administration will be critical in increasing our understanding of the processes of addiction and relapse, underlying mechanisms, and potential therapeutics. One system that has received considerable attention recently is the CRF1 system that may mediate the link between anxiety states and relapse drinking. C57BL/6J mice were trained to lever press for ethanol, were made dependent and then were allowed to self-administer ethanol following a period of abstinence. The effect of the CRF1 antagonist, antalarmin, was examined on this abstinence-induced self-administration in a separate group of mice. Finally, dependence-induced changes in ethanol self-administration were examined in CRF1 knockout and wild type mice. The results indicated that ethanol self-administration was increased following the induction of dependence, but only after a period of abstinence. This increase in ethanol self-administration was blocked by antalarmin. Furthermore, CRF1 knockout mice did not display this increased ethanol self-administration following dependence and abstinence. These studies, using both a pharmacological and genetic approach, support a critical role for the CRF1 system in ethanol self-administration following dependence. In addition, a model is presented that may be useful for studies examining underlying mechanisms of the ethanol addiction process as well as for testing potential therapeutics.
Keywords: Abstinence; Corticotropin-releasing factor; CRF1; dependence; Ethanol self-administration; Mouse

Development and resolution of brain lesions caused by pyrithiamine- and dietary-induced thiamine deficiency and alcohol exposure in the alcohol-preferring rat: a longitudinal magnetic resonance imaging and spectroscopy study - Pfefferbaum, Adolf; Adalsteinsson, Elfar; Bell, Richard L.; Sullivan, Edith V. (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2007)
Wernicke's encephalopathy (WE) is characterized by lesions in thalamus, hypothalamus (including mammillary nuclei), and inferior colliculi, results in serious disabilities, has an etiology of thiamine deficiency, is treatable with thiamine, and occurs most commonly with alcoholism. Despite decades of study, whether alcohol exposure exacerbates the neuropathology or retards its resolution remains controversial. To examine patterns of brain damage and recovery resulting from thiamine deprivation with and without alcohol exposure, we conducted in vivo magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) at 3 T in alcohol-preferring (P) rats, which had voluntarily consumed large amounts of alcohol before thiamine manipulation. A total of 18 adult male P rats (nine alcohol-exposed) received a thiamine-deficient diet for 2 weeks: 10 (five alcohol-exposed) received intraperitoneal (i.p.) pyrithiamine (PT) and eight (four alcohol-exposed) received i.p. thiamine supplementation. Neurological signs developed by day 14. Rats were scanned before thiamine depletion and 18 and 35 days after thiamine repletion. Two-dimensional J-resolved MRS single-voxel spectra with water reference were collected in a voxel subtending the thalamus; metabolite quantification was corrected for voxel tissue content. MRI identified significant enlargement of dorsal ventricles and increase in signal intensities in thalamus, inferior colliculi, and mammillary nuclei of PT compared with thiamine-treated (TT) groups from MRI 1-2, followed by significant normalization from MRI 2-3 in thalamus and colliculi, but not mammillary nuclei and lateral ventricles. Voxel-by-voxel analysis revealed additional hyperintense signal clusters in the dorsal and ventral hippocampus and enlargement of the fourth ventricle. MRS showed a significant decline and then partial recovery in thalamic N-acetylaspartate, a marker of neuronal integrity, in PT compared with TT rats, with no change detected in creatine, choline, or glutamate. PT rats with prior alcohol exposure exhibited attenuated recovery in the thalamus and arrested growth of the corpus callosum; further, two of the five alcohol-exposed PT rats died prematurely. Parenchymal and ventricular changes with thiamine manipulation concur with human radiological signs of WE. The enduring macrostructural and neurochemical abnormalities involving critical nodes of Papez circuit carry liabilities for development of amnesia and incomplete recovery from other cognitive and motor functions subserved by the affected neural systems.
Keywords: Alcohol-Induced Disorders; alcoholism; Animal; Animals; Antimetabolites; Biomarkers; Brain; Central Nervous System Depressants; Disease Models; Ethanol; Korsakoff Syndrome; Longitudinal Studies; Magnetic Resonance Imaging; Magnetic Resonance Spectroscopy; Male; Nerve Degeneration; Nervous System; Pyrithiamine; Rats; Survival Rate; Thiamine; Thiamine Deficiency; Wistar

Downregulation of mu opioid receptor by RNA interference in the ventral tegmental area reduces ethanol consumption in mice - Lasek, A. W.; Janak, P. H.; He, L.; Whistler, J. L.; Heberlein, U. (Genes, Brain, and Behavior, 2007)
Pharmacological and genetic studies have implicated the mu opioid receptor (MOR) in the regulation of ethanol intake in animal models and humans. Non-specific antagonists of opioid receptors have been shown to affect ethanol consumption when infused directly into the ventral tegmental area (VTA) of rats. However, administration of MOR-selective antagonists into the VTA has yielded mixed results. We used RNA interference (RNAi) to specifically decrease levels of MOR messenger RNA in the VTA of mice and examined the effect on ethanol consumption in a two-bottle choice paradigm. Mice were injected in the VTA with lentivirus expressing either a small hairpin RNA (shRNA) targeting MOR or a control shRNA. One week after virus injection, mice were examined for ethanol consumption in a two-bottle choice experiment with increasing concentrations of ethanol over the course of 1 month. Expression of an shRNA targeting MOR in the VTA led to a significant reduction in ethanol consumption. These results strengthen the hypothesis that MOR in the VTA is one of the key brain substrates mediating alcohol consumption. The RNAi combined with lentiviral delivery can be used successfully in brain to effect a sustained reduction in expression of specific genes for behavioral analysis.
Keywords: Administration; Alcohol Drinking; Animals; Choice Behavior; Dose-Response Relationship; Down-Regulation; Drug; Ethanol; Female; Gene Transfer Techniques; Inbred C57BL; Lentivirus; Messenger; Mice; mu; Opioid; Oral; Receptors; RNA; RNA Interference; Small Interfering; Ventral tegmental area

Drosophila homer is required in a small set of neurons including the ellipsoid body for normal ethanol sensitivity and tolerance - Urizar, Nancy L.; Yang, Zhiyong; Edenberg, Howard J.; Davis, Ronald L. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2007)
The molecular mechanisms occurring in the nervous system that underlie behavioral responses to ethanol remain poorly understood. Here, we report that molecular requirements for two of these responses, initial sensitivity and the development of rapid tolerance, comap to the same small set of neurons. We show that null homer mutant flies exhibit both increased sensitivity to the sedative effects of ethanol and failure to develop normal levels of rapid tolerance. Both the sensitivity and rapid tolerance phenotypes of the homer mutants are rescued by the expression of wild-type homer in a subset of neurons that include the ellipsoid body. Thus, some of the molecular- and systems-level requirements for these two behavioral responses to ethanol are identical.
Keywords: Animals; Brain; Carrier Proteins; Central Nervous System Depressants; DNA-Binding Proteins; Drosophila melanogaster; Drosophila Proteins; Drug Resistance; Drug Tolerance; Ethanol; Genetically Modified; Homer Scaffolding Proteins; Male; Neurons; Oligonucleotide Array Sequence Analysis; Phenotype; Saccharomyces cerevisiae Proteins; Transcription Factors

Ethanol preference is inversely correlated with ethanol-induced dopamine release in 2 substrains of C57BL/6 mice - Ramachandra, Vorani; Phuc, Steven; Franco, Ana Crystal; Gonzales, Rueben A. (Alcoholism, Clinical and Experimental Research, 2007)
BACKGROUND: The C57BL/6 mouse model has been used extensively in alcohol drinking studies, yet significant differences in ethanol preference between substrains exist. Differences in ethanol-induced dopamine release in the ventral striatum could contribute to this variability in drinking behavior as dopamine has been implicated in the reinforcing properties of ethanol. METHODS: A 2-bottle choice experiment investigated the difference in ethanol preference between C57BL/6J and C57BL/6NCrl animals. Microdialysis was used to determine dopamine release and ethanol clearance in these 2 substrains after intraperitoneal injections of 1.0, 2.0 and 3.0 g/kg ethanol or saline. RESULTS: C57BL/6J mice exhibited significantly greater ethanol preference and less ethanol-stimulated dopamine release compared with C57BL/6NCrl mice. The intraperitoneal injections of ethanol caused a significant increase in dopamine in both substrains at all 3 doses with significant differences between substrains at the 2 highest alcohol doses. Saline injections had a significant effect on dopamine release when given in a volume equivalent to the 3 g/kg ethanol dose. Ethanol pharmacokinetics were similar in the 2 substrains at all 3 doses. CONCLUSIONS: Ethanol-induced dopamine release in the ventral striatum may contribute to the differences in alcohol preference between C57BL/6J and C57BL/6NCrl mice.
Keywords: Alcohol Drinking; Animal; Animals; Basal Ganglia; Behavior; Central Nervous System Depressants; dopamine; Dose-Response Relationship; Drug; Ethanol; Inbred C57BL; Male; Mice

FOS expression induced by an ethanol-paired conditioned stimulus - Hill, Katherine G.; Ryabinin, Andrey E.; Cunningham, Christopher L. (Pharmacology, Biochemistry, and Behavior, 2007)
To identify brain areas involved in ethanol-induced Pavlovian conditioning, brains of male DBA/2J mice were immunohistochemically analyzed for FOS expression after exposure to a conditioned stimulus (CS) previously paired with ethanol (2 g/kg) in two experiments. Mice were trained with a procedure that normally produces place preference (Before: ethanol before the CS) or one that normally produces place aversion (After: ethanol after the CS). Control groups received unpaired ethanol injections in the home cage (Delay) or saline only (Naïve). On the test day, mice were exposed to the 5-min CS 90 min before sacrifice. Before groups showed a conditioned increase in activity, whereas the After group showed a conditioned decrease in activity. FOS expression after a drug-free CS exposure was significantly higher in Before-group mice than in control mice in the bed nucleus of the stria terminalis (Experiment 1) and anterior ventral tegmental area (Experiments 1-2). Conditioned FOS responses were also seen in areas of the extended amygdala and hippocampus (Experiment 2). However, no conditioned FOS changes were seen in any brain area examined in After-group mice. Overall, these data suggest an important role for the mesolimbic dopamine pathway, extended amygdala and hippocampus in ethanol-induced conditioning.
Keywords: Animals; Brain Chemistry; Central Nervous System Depressants; Conditioning; Ethanol; fos; Gene Expression; Genes; Immunohistochemistry; Inbred DBA; Male; Mice; Motor Activity; Operant; Reproducibility of Results

Functional gene expression differences between inbred alcohol-preferring and –non-preferring rats in five brain regions - Kimpel, Mark W.; Strother, Wendy N.; McClintick, Jeanette N.; Carr, Lucinda G.; Liang, Tiebing; Edenberg, Howard J.; McBride, William J. (Alcohol, 2007)
The objective of this study was to determine if there are innate differences in gene expression in selected CNS regions between inbred alcohol-preferring (iP) and –non-preferring (iNP) rats. Gene expression was determined in the nucleus accumbens (ACB), amygdala (AMYG), frontal cortex (FC), caudate-putamen (CPU), and hippocampus (HIPP) of alcohol-naïve adult male iP and iNP rats, using Affymetrix Rat Genome U34A microarrays (n = 6/strain). Using Linear Modeling for Microarray Analysis with a false discovery rate threshold of 0.1, there were 16 genes with differential expression in the ACB, 54 in the AMYG, 8 in the FC, 24 in the CPU, and 21 in the HIPP. When examining the main effect of strain across regions, 296 genes were differentially expressed. Although the relatively small number of genes found significant within individual regions precluded a powerful analysis for over-represented Gene Ontology categories, the much larger list resulting from the main effect of strain analysis produced 17 over-represented categories (P < .05), including axon guidance, gliogenesis, negative regulation of programmed cell death, regulation of programmed cell death, regulation of synapse structure function, and transmission of nerve impulse. Co-citation analysis and graphing of significant genes revealed a network involved in the neuropeptide Y (NPY) transmitter system. Correlation of all significant genes with those located within previously established rat alcohol QTLs revealed that of the total of 313 significant genes, 71 are located within such QTLs. The many regional and overall gene expression differences between the iP and iNP rat lines may contribute to the divergent alcohol drinking phenotypes of these rats.
Keywords: Alcohol-preferring P rat; Alcohol–non-preferring NP rat; Amygdala; Caudate-putamen; Frontal cortex; Gene Expression; Hippocampus; Microarrays; Nucleus Accumbens

GABAergic modulation of binge-like ethanol intake in C57BL/6J mice - Moore, Eileen M.; Serio, Kristen M.; Goldfarb, Karen J.; Stepanovska, Sandra; Linsenbardt, David N.; Boehm, Stephen L. (Pharmacology, Biochemistry, and Behavior, 2007)
GABA receptor systems have long been implicated in alcoholism, and GABAergic drugs have demonstrated efficacy in altering alcohol intake in some rodent models. The present study was designed to assess the effects of baclofen, muscimol, and gaboxadol (THIP) in a variation on a new mouse model of binge-like ethanol intake. Three hours into their dark cycle, male and female C57BL/6J mice were given access to a 20% unsweetened ethanol solution for 2 h each day, for four days. On day five, mice received varying doses of baclofen, muscimol or THIP and were allowed access to 20% ethanol for 60 min. Baclofen dose-dependently increased binge-like ethanol intake, while both muscimol and THIP reduced ethanol intake. Subsequent studies testing the effect of baclofen, muscimol and THIP on water intake using the same procedure revealed that whereas baclofen had no significant effect, muscimol and THIP both reduced the measure. These results add to the growing literature suggesting a role for GABA receptor systems in the modulation of ethanol intake. However, whereas the role of GABA(B) receptor systems seems selective in the modulation of binge-like ethanol intake, the role for GABA(A) receptor systems appears to also extend to general fluid intake.
Keywords: alcoholism; Animals; Baclofen; Central Nervous System Depressants; Darkness; Dose-Response Relationship; Drug; Ethanol; Female; GABA Agonists; GABA Antagonists; gamma-Aminobutyric Acid; Inbred C57BL; Isoxazoles; Male; Mice; Muscimol; Postural Balance

Identification of novel striatal genes by expression profiling in adult mouse brain - Ghate, A.; Befort, K.; Becker, J. a. J.; Filliol, D.; Bole-Feysot, C.; Demebele, D.; Jost, B.; Koch, M.; Kieffer, B. L. (Neuroscience, 2007)
Large-scale transcriptome analysis in the brain is a powerful approach to identify novel genes of potential interest toward understanding cerebral organization and function. We utilized the microarray technology to measure expression levels of about 24,000 genes and expressed sequence tags in mouse hippocampus, frontal cortex and striatum. Using expression profile obtained from whole brain as a reference, we categorized the genes into groups of genes either enriched in, or restricted to, one of the three areas of interest. We found enriched genes for each target area. Further, we identified 14 genes in the category of genes restricted to the striatum, among which were the orphan G protein-coupled receptor GPR88 and retinoic acid receptor-beta. These two genes were already reported to be selectively expressed in the striatum, thus validating our experimental approach. We selected 6 striatal-restricted genes, as well as 10 striatal-enriched candidates, that were previously undescribed. We analyzed their expression by in situ hybridization analysis in the brain, and quantitative RT-PCR in both brain and peripheral organs. Two of these unknown genes displayed a notable expression pattern. The striatal-restricted gene H3076B11 shows uniform expression throughout and uniquely in the striatum, representing a genuine striatal marker. The striatal-enriched gene 4833421E05Rik is preferentially expressed in the rostral striatum, and is also abundant in kidney, liver and lung. These two genes may contribute to some of the many striatal-controlled behaviors, including initiation of movement, habit formation, or reward and motivation.
Keywords: Animals; Brain Chemistry; Complementary; Data Interpretation; DNA; Gene Expression Profiling; In Situ Hybridization; Inbred C57BL; Mice; Neostriatum; Nerve Tissue Proteins; Oligonucleotide Array Sequence Analysis; Receptors; Retinoic Acid; Reverse Transcriptase Polymerase Chain Reaction; RNA; Statistical

In vivo fiber tracking in the rat brain on a clinical 3T MRI system using a high strength insert gradient coil - Mayer, Dirk; Zahr, Natalie M.; Adalsteinsson, Elfar; Rutt, Brian; Sullivan, Edith V.; Pfefferbaum, Adolf (NeuroImage, 2007)
In vivo neuroimaging methods permit longitudinal quantitative examination of the dynamic course of neurodegenerative conditions in humans and animal models and enable assessment of therapeutic efforts in mitigating disease effects on brain systems. The study of conditions affecting white matter, such as multiple sclerosis, demyelinating conditions, and drug and alcohol dependence, can be accomplished with diffusion tensor imaging (DTI), a technique uniquely capable of probing the microstructural integrity of white matter fibers in the living brain. We used a 3T clinical MR scanner equipped with an insert gradient coil that yields an order of magnitude increase in performance over the whole-body hardware to acquire in vivo DTI images of rat brain. The resolution allowed for fiber tracking evaluation of fractional anisotropy (FA) and apparent diffusion coefficients in the genu and splenium of the corpus callosum. A comparison of short (46 min) and long (92 min) acquisition time DTI protocols indicated low but adequate signal-to-noise ratio (SNR=6.2) of the shorter protocol to conduct quantitative fiber tracking enhanced by multiple acquisitions. As observed in human studies, FA in the rat splenium was higher than in the genu. Advantages of this technology include the use of similar user interface, pulse sequences, and field strength for preclinical animal and clinical human research, enhancing translational capabilities. An additional benefit of scanning at lower field strength, such as 3 T, is the reduction of artifacts due to main field inhomogeneity relative to higher field animal systems.
Keywords: Animals; Corpus Callosum; Equipment Design; Equipment Failure Analysis; Image Enhancement; Magnetic Resonance Imaging; Male; Nerve Fibers; Neural Pathways; Rats; Reproducibility of Results; Sensitivity and Specificity; Transducers; Wistar

In vivo metabolite differences between the basal ganglia and cerebellum of the rat brain detected with proton MRS at 3T - Mayer, Dirk; Zahr, Natalie M.; Sullivan, Edith V.; Pfefferbaum, Adolf (Psychiatry Research, 2007)
In vivo magnetic resonance spectroscopy (MRS) enables non-invasive longitudinal tracking of brain chemistry changes that can accompany aging, neurodegenerative disease, drug addiction and experimental manipulations in animals modeling such conditions. J-coupled resonances, such as glutamate, which are highly relevant to neuropsychiatric conditions are difficult to resolve on a clinical 3T MR scanner using conventional one-dimensional MRS sequences. We, therefore, implemented Constant Time PRESS (CT-PRESS) to quantify major metabolite and neurotransmitter biochemical signals, including glutamate, in two brain regions of the rat, basal ganglia and cerebellum. We acquired spectra at two distinct time points in two independent groups of six rats and analyzed metabolite levels using either creatine or water as a reference. Our results provide evidence that CT-PRESS at 3T is adequate and reliable for in vivo detection and quantification of glutamate in the rat brain and that regional differences occur in the signal intensities of the major metabolites. That the directionality of the differences depends on whether creatine or water is used as a reference for metabolite levels emphasizes the benefit to in vivo MRS of incorporating methods to establish absolute baseline metabolite concentrations.
Keywords: Animals; Basal Ganglia; Cerebellum; Glutamic Acid; Magnetic Resonance Spectroscopy; Male; Rats; Signal Transduction; Wistar

Increased drinking during withdrawal from intermittent ethanol exposure is blocked by the CRF receptor antagonist D-Phe-CRF(12-41) - Finn, Deborah A.; Snelling, Christopher; Fretwell, Andrea M.; Tanchuck, Michelle A.; Underwood, Lisa; Cole, Maury; Crabbe, John C.; Roberts, Amanda J. (Alcoholism, Clinical and Experimental Research, 2007)
BACKGROUND: Studies in rodents have determined that intermittent exposure to alcohol vapor can increase subsequent ethanol self-administration, measured with operant and 2-bottle choice procedures. Two key procedural factors in demonstrating increased alcohol intake are the establishment of stable alcohol self-administration before alcohol vapor exposure and the number of bouts of intermittent vapor exposure. The present studies provide additional behavioral validation and initial pharmacological validation of this withdrawal-associated drinking procedure. METHODS: Studies at 2 different sites (Portland and Scripps) examined the effect of intermittent ethanol vapor exposure (3 cycles of 16 hours of ethanol vapor+8 hours air) on 2-hour limited access ethanol preference drinking in male C57BL/6 mice. Separate studies tested 10 or 15% (v/v) ethanol concentrations, and measured intake during the circadian dark. In one study, before measuring ethanol intake after the second bout of intermittent vapor exposure, mice were tested for handling-induced convulsions (HICs) indicative of physical dependence on ethanol. In a second study, the effect of bilateral infusions of the corticotropin-releasing factor (CRF) receptor antagonist D-Phe-CRF(12-41) (0.25 microg/0.5 microL) into the central nucleus of the amygdala (CeA) on ethanol intake was compared in vapor-exposed animals and air controls. RESULTS: Intermittent ethanol vapor exposure significantly increased ethanol intake by 30 to 40%, and the mice had higher blood ethanol concentrations than controls. Intra-amygdala infusions of D-Phe-CRF(12-41) significantly decreased the withdrawal-associated increase in ethanol intake without altering ethanol consumption in controls. Following the second bout of intermittent vapor exposure, mice exhibited an increase in HICs, when compared with their own baseline scores or the air controls. CONCLUSIONS: Intermittent alcohol vapor exposure significantly increased alcohol intake and produced signs of physical dependence. Initial pharmacological studies suggest that manipulation of the CRF system in the CeA can block this increased alcohol intake.
Keywords: Alcohol Drinking; Amygdala; Animals; Central Nervous System Depressants; Corticotropin-Releasing Hormone; Ethanol; Injections; Male; Mice; Receptors; Substance Withdrawal Syndrome

Influence of reinforcement schedule on ethanol consumption patterns in non-food restricted male C57BL/6J mice - Ford, Matthew M.; Fretwell, Andrea M.; Mark, Gregory P.; Finn, Deborah A. (Alcohol (Fayetteville, N.Y.), 2007)
Ethanol reinforcement should ideally be evaluated in animals that are not food deprived to ensure that the motivation behind its consumption is pharmacological, and not caloric, in nature. The objective of this work was to assess the influence of reinforcement schedule on ethanol intake in nondeprived mice. Male C57BL/6J mice were trained to respond on an ethanol-reinforced lever on a fixed ratio 4 reinforcement schedule for 10% ethanol (10E). The appetitive and consummatory phases were then procedurally separated by changing the response requirement (RR), so that mice were permitted 30-min continuous 10E access after completion of either four (RR4) or eight (RR8) responses. Phase separation yielded a heightened appetitive drive to acquire 10E access (as indexed by a significant decrease in the latency to first active lever and a trend toward a decrease in the latency to first sipper contact) and an augmented level of drinking (twofold elevation in the ethanol dose consumed). Robust extinction responding on the ethanol-appropriate lever indicated that ethanol was effective as a behavioral reinforcer. These results suggest that the separation of appetitive and consummatory phases of ethanol self-administration may prove useful in future evaluations of the pharmacological and genetic bases of ethanol reinforcement in mice.
Keywords: Alcohol Drinking; Animal; Animals; Appetitive Behavior; Behavior; Central Nervous System Depressants; Conditioning; Consummatory Behavior; Eating; Ethanol; Extinction; Inbred C57BL; Male; Mice; Models; Motivation; Operant; Psychological; Reaction Time; Reinforcement Schedule; Self Administration

Interaction of thiamine deficiency and voluntary alcohol consumption disrupts rat corpus callosum ultrastructure - He, Xiaohua; Sullivan, Edith V.; Stankovic, Roger K.; Harper, Clive G.; Pfefferbaum, Adolf (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2007)
The relative roles of alcohol and thiamine deficiency in causing brain damage remain controversial in alcoholics without the Wernicke-Korsakoff syndrome. Experimental control over alcohol consumption and diet are impossible in humans but can be accomplished in animal models. This experiment was designed to differentiate the separate and combined effects on the macro- and ultrastructure of the corpus callosum of thiamine deficiency and voluntary alcohol consumption. Adult male alcohol-preferring (P) rats (9 chronically alcohol-exposed and 9 water controls) received a thiamine-deficient diet for 2 weeks. There were four groups: five rats previously exposed to alcohol were treated with pyrithiamine (a thiamine phosphorylation inhibitor); five rats never exposed to alcohol were treated with pyrithiamine; four alcohol-exposed rats were treated with thiamine; and four rats never exposed to alcohol were treated with thiamine. On day 14, thiamine was restored in all 18 rats; 2 weeks later the 10 pyrithiamine-treated rats received intraperitoneal thiamine. The rats were perfused 61 days post-pyrithiamine treatment at age 598 days. Brains were dissected and weight and volumes were calculated. Sagittal sections were stained to measure white matter structures. The corpus callosum was examined using transmission electron microscopy to determine density of myelinated fibers, fiber diameter, and myelin thickness. The corpus callosum in the alcohol/pyrithiamine group was significantly thinner, had greater fiber density, higher percentage of small fibers, and myelin thinning than in the alcohol/thiamine and water/thiamine groups. Several measures showed a graded effect, where the alcohol/pyrithiamine group had greater pathology than the water/pyrithiamine group, which had greater pathology than the two thiamine-replete groups. Across all 16 rats, thinner myelin sheaths correlated with higher percentage of small fibers. Myelin thickness and axon diameter together accounted for 71% of the variance associated with percentage of small fibers. Significant abnormalities in the alcohol/pyrithiamine group and lack of abnormality in the alcohol-exposed/thiamine-replete group indicate that thiamine deficiency caused white matter damage. The graded abnormalities across the dually to singly treated animals support a compounding effect of alcohol exposure and thiamine depletion, and indicate the potential for interaction between alcohol and thiamine deficiency in human alcohol-related brain damage.
Keywords: Alcohol-Induced Disorders; alcoholism; Animals; Antimetabolites; Atrophy; Central Nervous System Depressants; Corpus Callosum; Ethanol; Mutant Strains; Myelinated; Nerve Fibers; Nervous System; Pyrithiamine; Rats; Thiamine Deficiency; Wallerian Degeneration; Wistar

Mouse inbred strain differences in ethanol drinking to intoxication - Rhodes, J. S.; Ford, M. M.; Yu, C.-H.; Brown, L. L.; Finn, D. A.; Garland, T.; Crabbe, J. C. (Genes, Brain, and Behavior, 2007)
Recently, we described a simple procedure, Drinking in the Dark (DID), in which C57BL/6J mice self-administer ethanol to a blood ethanol concentration (BEC) above 1 mg/ml. The test consists of replacing the water with 20% ethanol in the home cage for 4 h early during the dark phase of the light/dark cycle. Three experiments were conducted to explore this high ethanol drinking model further. In experiment 1, a microanalysis of C57BL/6J behavior showed that the pattern of ethanol drinking was different from routine water intake. In experiment 2, drinking impaired performance of C57BL/6J on the accelerating rotarod and balance beam. In experiment 3, 12 inbred strains were screened to estimate genetic influences on DID and correlations with other traits. Large, reliable differences in intake and BEC were detected among the strains, with C57BL/6J showing the highest values. Strain means were positively correlated with intake and BEC in the standard (24 h) and a limited (4 h) two-bottle ethanol vs. water test, but BECs reached higher levels for DID. Strain mean correlations with other traits in the Mouse Phenome Project database supported previously reported genetic relationships of high ethanol drinking with low chronic ethanol withdrawal severity and low ethanol-conditioned taste aversion. We extend these findings by showing that the correlation estimates remain relatively unchanged even after correcting for phylogenetic relatedness among the strains, thus relaxing the assumption that the strain means are statistically independent. We discuss applications of the model for finding genes that predispose pharmacologically significant drinking in mice.
Keywords: Alcohol Drinking; Alcoholic Intoxication; Animal; Animals; Behavioral; Choice Behavior; Darkness; Disease Models; Drinking Behavior; Ethanol; Female; Genetic Variation; Genetics; Inbred C57BL; Inbred Strains; Male; Mice; Phylogeny; Rotarod Performance Test; Self Administration; Sex Factors; Species Specificity

Mu (mu) opioid receptor regulation of ethanol-induced dopamine response in the ventral striatum: evidence of genotype specific sexual dimorphic epistasis - Job, Martin O.; Tang, Amanda; Hall, F. Scott; Sora, Ichiro; Uhl, George R.; Bergeson, Susan E.; Gonzales, Rueben A. (Biological Psychiatry, 2007)
BACKGROUND: Ethanol stimulates the dopaminergic mesoaccumbal pathway, which is thought to play a role in ethanol reinforcement. Mu (mu)-opioid (MOP) receptors modulate accumbal dopamine activity, but it is not clear whether MOP receptors are involved in the mechanism of ethanol-stimulated accumbal dopamine release. METHODS: We investigated the role that MOP receptors play in ethanol (2.0 g/kg)-stimulated accumbal dopamine release by using MOP receptor knockout mice (C57BL/6J-129SvEv and congenic C57BL/6J genotypes) along with blockade of MOP receptors with a mu1 selective antagonist (naloxonazine). RESULTS: Both gene deletion and pharmacological antagonism of the MOP receptor decreased ethanol-stimulated accumbal dopamine release compared with controls with female mice showing a larger effect in the C57BL/6J-129SvEv genotype. However, both male and female mice showed reduced ethanol-stimulated dopamine release in the congenic MOP receptor knockout mice (C57BL/6J). No differences in the time course of dialysate ethanol concentration were found in any of the experiments. CONCLUSIONS: The data demonstrate the existence of a novel interaction between genotype and sex in the regulation of ethanol-stimulated mesolimbic dopamine release by the MOP receptor. This implies that a more complete understanding of the epistatic influences on the MOP receptor and mesolimbic dopamine function may provide more effective pharmacotherapeutic interventions in the treatment of alcoholism.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Basal Ganglia; Congenic; Disease Models; dopamine; Epistasis; Ethanol; Genetic; Genotype; Humans; Inbred C57BL; Knockout; Mice; Microdialysis; mu; Naloxone; Nucleus Accumbens; Opioid; Receptors; Reinforcement (Psychology); Sex Characteristics

Neuroadaptations in Human Chronic Alcoholics: Dysregulation of the NF-κB System - Ökvist, Anna; Johansson, Sofia; Kuzmin, Alexander; Bazov, Igor; Merino-Martinez, Roxana; Ponomarev, Igor; Mayfield, R. Dayne; Harris, R. Adron; Sheedy, Donna; Garrick, Therese; Harper, Clive; Hurd, Yasmin L.; et al. (PLOS ONE, 2007)
BackgroundAlcohol dependence and associated cognitive impairments apparently result from neuroadaptations to chronic alcohol consumption involving changes in expression of multiple genes. Here we investigated whether transcription factors of Nuclear Factor-kappaB (NF-κB) family, controlling neuronal plasticity and neurodegeneration, are involved in these adaptations in human chronic alcoholics.Methods and FindingsAnalysis of DNA-binding of NF-κB (p65/p50 heterodimer) and the p50 homodimer as well as NF-κB proteins and mRNAs was performed in postmortem human brain samples from 15 chronic alcoholics and 15 control subjects. The prefrontal cortex involved in alcohol dependence and cognition was analyzed and the motor cortex was studied for comparison. The p50 homodimer was identified as dominant κB binding factor in analyzed tissues. NF-κB and p50 homodimer DNA-binding was downregulated, levels of p65 (RELA) mRNA were attenuated, and the stoichiometry of p65/p50 proteins and respective mRNAs was altered in the prefrontal cortex of alcoholics. Comparison of a number of p50 homodimer/NF-κB target DNA sites, κB elements in 479 genes, down- or upregulated in alcoholics demonstrated that genes with κB elements were generally upregulated in alcoholics. No significant differences between alcoholics and controls were observed in the motor cortex.ConclusionsWe suggest that cycles of alcohol intoxication/withdrawal, which may initially activate NF-κB, when repeated over years downregulate RELA expression and NF-κB and p50 homodimer DNA-binding. Downregulation of the dominant p50 homodimer, a potent inhibitor of gene transcription apparently resulted in derepression of κB regulated genes. Alterations in expression of p50 homodimer/NF-κB regulated genes may contribute to neuroplastic adaptation underlying alcoholism.
Keywords: Alcohol consumption; Alcoholics; alcoholism; DNA transcription; DNA-Binding Proteins; Gene Expression; Prefrontal Cortex; Transcription Factors

The PhenoGen informatics website: tools for analyses of complex traits - Bhave, Sanjiv V.; Hornbaker, Cheryl; Phang, Tzu L.; Saba, Laura; Lapadat, Razvan; Kechris, Katherina; Gaydos, Jeanette; McGoldrick, Daniel; Dolbey, Andrew; Leach, Sonia; Soriano, Brian; Ellington, Allison; et al. (BMC genetics, 2007)
BACKGROUND: With the advent of "omics" (e.g. genomics, transcriptomics, proteomics and phenomics), studies can produce enormous amounts of data. Managing this diverse data and integrating with other biological data are major challenges for the bioinformatics community. Comprehensive new tools are needed to store, integrate and analyze the data efficiently. DESCRIPTION: The PhenoGen Informatics website http://phenogen.uchsc.edu is a comprehensive toolbox for storing, analyzing and integrating microarray data and related genotype and phenotype data. The site is particularly suited for combining QTL and microarray data to search for "candidate" genes contributing to complex traits. In addition, the site allows, if desired by the investigators, sharing of the data. Investigators can conduct "in-silico" microarray experiments using their own and/or "shared" data. CONCLUSION: The PhenoGen website provides access to tools that can be used for high-throughput data storage, analyses and interpretation of the results. Some of the advantages of the architecture of the website are that, in the future, the present set of tools can be adapted for the analyses of any type of high-throughput "omics" data, and that access to new tools, available in the public domain or developed at PhenoGen, can be easily provided.
Keywords: Database Management Systems; Databases; Gene Expression Profiling; Genetic; Genomics; Internet; Quantitative Trait Loci

Predicting combinatorial binding of transcription factors to regulatory elements in the human genome by association rule mining - Morgan, Xochitl C.; Ni, Shulin; Miranker, Daniel P.; Iyer, Vishwanath R. (BMC Bioinformatics, 2007)
Cis-acting transcriptional regulatory elements in mammalian genomes typically contain specific combinations of binding sites for various transcription factors. Although some cis-regulatory elements have been well studied, the combinations of transcription factors that regulate normal expression levels for the vast majority of the 20,000 genes in the human genome are unknown. We hypothesized that it should be possible to discover transcription factor combinations that regulate gene expression in concert by identifying over-represented combinations of sequence motifs that occur together in the genome. In order to detect combinations of transcription factor binding motifs, we developed a data mining approach based on the use of association rules, which are typically used in market basket analysis. We scored each segment of the genome for the presence or absence of each of 83 transcription factor binding motifs, then used association rule mining algorithms to mine this dataset, thus identifying frequently occurring pairs of distinct motifs within a segment.

Presynaptic delta opioid receptors regulate ethanol actions in central amygdala - Kang-Park, Maeng-Hee; Kieffer, Brigitte L.; Roberts, Amanda J.; Siggins, George Robert; Moore, Scott D. (The Journal of Pharmacology and Experimental Therapeutics, 2007)
Endogenous opioid systems are implicated in the reinforcing effects of ethanol consumption. For example, delta opioid receptor (DOR) knockout (KO) mice show greater ethanol consumption than wild-type (WT) mice (Roberts et al., 2001). To explore the neurobiological correlates underlying these behaviors, we examined effects of acute ethanol application in brain slices from DOR KO mice using whole-cell patch recording techniques. We examined the central nucleus of amygdala (CeA) because the CeA is implicated in alcohol reinforcement (Koob et al., 1998). We found that the acute ethanol effects on GABA(A) receptor-mediated inhibitory postsynaptic currents (IPSCs) were greater in DOR KO mice than in WT mice. Ethanol increased the frequency of miniature IPSCs (mIPSCs) significantly more in DOR KO mice than in WT mice. In CeA of WT mice, application of ICI 174864 [[allyl]2-Tyr-alpha-amino-isobutyric acid (Aib)-Aib-Phe-Leu-OH], a DOR inverse agonist, augmented ethanol actions on mIPSC frequency comparable with ethanol effects seen in DOR KO mice. Superfusion of the selective DOR agonist D-Pen(2),D-Pen(5)-enkephalin decreased the mean frequency of mIPSCs; this effect was reversed by the DOR antagonist naltrindole. These findings suggest that endogenous opioids may reduce ethanol actions on IPSCs of CeA neurons in WT mice through DOR-mediated inhibition of GABA release and that the increased ethanol effect on IPSCs in CeA of DOR KO mice could be, at least in part, due to absence of DOR-mediated inhibition of GABA release. This result supports the hypothesis that endogenous opioid peptides modulate the ethanol-induced augmentation of GABA(A) receptor-dependent circuitry in CeA (Roberto et al., 2003).
Keywords: 5)-; Amygdala; Animals; D-Penicillamine (2; delta; Enkephalin; Ethanol; GABA-A; gamma-Aminobutyric Acid; Inbred C57BL; Inhibitory Postsynaptic Potentials; Leucine; Male; Mice; Opioid; Receptors

Robust and Stable Drinking Behavior Following Long-Term Oral Alcohol Intake In Rhesus Macaques - Katner, Simon N.; Von Huben, Stefani N.; Davis, Sophia A.; Lay, Christopher C.; Crean, Rebecca D.; Roberts, Amanda J.; Fox, Howard S.; Taffe, Michael A. (Drug and alcohol dependence, 2007)
Face validity in animal models of alcohol abuse and dependence is often at odds with robust demonstrations of ethanol-seeking. This study determined the relative influence of ethanol and a flavorant in maintaining ethanol intake in a nonhuman primate model of “cocktail” drinking. Four year old male monkeys were maintained on a 6% ethanol/6% Tang® solution made available in daily (M-F) 1-hr sessions. Experiments determined the effect of: 1) a second daily access session, 2) concurrent presentation of the Tang® vehicle, 3) sequential presentation of the vehicle in the first daily session and the ethanol solution in the second session, 4) altering the Tang® concentration, 5) altering the ethanol concentration, and 6) removal of the flavorant. Mean daily intake (2.7 ± 0.2 g/kg/day) was stable over 7 months. Simultaneous availability of a large, but not a low-moderate, volume of the vehicle reduced ethanol intake by about 50%. Decreasing the concentration of Tang® in the first daily session reduced ethanol intake whereas intake of the standard solution was increased in the second session. Ethanol consumption was decreased by only 27% when the flavorant was removed. In summary, alterations that reduced intake in the first daily session resulted in compensatory increases in ethanol intake in the second session suggesting that animals sought a specific level of ethanol intake per day. It is concluded that models with excellent face validity (flavored beverages) can produce reliable ethanol intake in patterns that are highly consistent with ethanol-seeking behavior.

Role of endocannabinoids in alcohol consumption and intoxication: studies of mice lacking fatty acid amide hydrolase - Blednov, Yuri A.; Cravatt, Benjamin F.; Boehm, Stephen L.; Walker, Danielle; Harris, R. Adron (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2007)
Endocannabinoid signaling plays the important role in regulation of ethanol intake. Fatty acid amide hydrolase (FAAH) is a key membrane protein for metabolism of endocannabinoids, including anandamide, and blockade of FAAH increases the level of anandamide in the brain. To determine if FAAH regulates ethanol consumption, we studied mutant mice with deletion of the FAAH gene. Null mutant mice showed higher preference for alcohol and voluntarily consumed more alcohol than wild-type littermates. There was no significant difference in consumption of sweet or bitter solutions. To determine the specificity of FAAH for ethanol intake, we studied additional ethanol-related behaviors. There were no differences between null mutant and wild-type mice in severity of ethanol-induced acute withdrawal, conditioned taste aversion to alcohol, conditioned place preference, or sensitivity to hypnotic effect of ethanol. However, null mutant mice showed shorter duration of loss of righting reflex induced by low doses of ethanol (3.2 and 3.4 g/kg) and faster recovery from motor incoordination induced by ethanol. All three behavioral phenotypes (increased preference for ethanol, decreased sensitivity to ethanol-induced sedation, and faster recovery from ethanol-induced motor incoordination) seen in mutant mice were reproduced in wild-type mice by injection of a specific inhibitor of FAAH activity–URB597. These data suggest that increased endocannabinoid signaling increased ethanol consumption owing to decreased acute ethanol intoxication.
Keywords: Alcohol-Induced Disorders; Amidohydrolases; Animals; Avoidance Learning; Brain; Brain Chemistry; Cannabinoid Receptor Modulators; Endocannabinoids; Enzyme Inhibitors; Ethanol; Fatty Acids; Female; Genetic Predisposition to Disease; Inbred C57BL; Knockout; Male; Metabolic Clearance Rate; Mice; Movement Disorders; Nervous System; Recovery of Function; Sex Characteristics; Substance Withdrawal Syndrome

SNPs matter: impact on detection of differential expression - Walter, Nicole A. R.; McWeeney, Shannon K.; Peters, Sandra T.; Belknap, John K.; Hitzemann, Robert; Buck, Kari J. (Nature Methods, 2007)
Keywords: Animals; Base Sequence; Databases; False Negative Reactions; Gene Expression; Genetic; Genome; Inbred C57BL; Inbred DBA; Mice; Molecular Sequence Data; Oligonucleotide Array Sequence Analysis; Polymorphism; Sensitivity and Specificity; Single Nucleotide; Species Specificity

Actions of Acute and Chronic Ethanol on Presynaptic Terminals - Roberto, Marisa; Treistman, Steven N.; Pietrzykowski, Andrzej Z.; Weiner, Jeff; Galindo, Rafael; Mameli, Manuel; Valenzuela, Fernando; Zhu, Ping Jun; Lovinger, David; Zhang, Tao A.; Hendricson, Adam H.; Morrisett, Richard; et al. (Alcoholism, clinical and experimental research, 2006)
This article presents the proceedings of a symposium entitled “The Tipsy Terminal: Presynaptic Effects of Ethanol” (held at the annual meeting of the Research Society on Alcoholism, in Santa Barbara, CA, June 27, 2005). The objective of this symposium was to focus on a cellular site of ethanol action underrepresented in the alcohol literature, but quickly becoming a “hot” topic. The chairs of the session were Marisa Roberto and George Robert Siggins. Our speakers were chosen on the basis of the diverse electrophysiological and other methods used to discern the effects of acute and chronic ethanol on presynaptic terminals and on the basis of significant insights that their data provide for understanding ethanol actions on neurons in general, as mechanisms underlying problematic behavioral effects of alcohol. The 5 presenters drew from their recent studies examining the effects of acute and chronic ethanol using a range of sophisticated methods from electrophysiological analysis of paired-pulse facilitation and spontaneous and miniature synaptic currents (Drs. Weiner, Valenzuela, Zhu, and Morrisett), to direct recording of ion channel activity and peptide release from acutely isolated synaptic terminals (Dr. Treistman), to direct microscopic observation of vesicular release (Dr. Morrisett). They showed that ethanol administration could both increase and decrease the probability of release of different transmitters from synaptic terminals. The effects of ethanol on synaptic terminals could often be correlated with important behavioral or developmental actions of alcohol. These and other novel findings suggest that future analyses of synaptic effects of ethanol should attempt to ascertain, in multiple brain regions, the role of presynaptic terminals, relevant presynaptic receptors and signal transduction linkages, exocytotic mechanisms, and their involvement in alcohol’s behavioral actions. Such studies could lead to new treatment strategies for alcohol intoxication, alcohol abuse, and alcoholism.

The alcohol-preferring P rat and animal models of excessive alcohol drinking - Bell, Richard L.; Rodd, Zachary A.; Lumeng, Lawrence; Murphy, James M.; McBride, William J. (Addiction Biology, 2006)
The alcohol-preferring, P, rat was developed by selective breeding to study ethanol drinking behavior and its consequences. Characterization of this line indicates the P rat meets all of the criteria put forth for a valid animal model of alcoholism, and displays, relative to their alcohol-non-preferring, NP, counterparts, a number of phenotypic traits associated with alcohol abuse and alcoholism. Behaviorally, compared with NP rats, P rats are less sensitive to the sedative and aversive effects of ethanol and more sensitive to the stimulatory effects of ethanol. Neurochemically, research with the P line indicates the endogenous dopaminergic, serotonergic, GABAergic, opiodergic, and peptidergic systems may be involved in a predisposition for alcohol abuse and alcoholism. Paralleling the clinical literature, genetically selected P rats display levels of ethanol intake during adolescence comparable to that seen during adulthood. Binge drinking has been associated with an increased risk for health and other problems associated with ethanol abuse. A model of binge-like drinking during the dark cycle indicates that P rats will consume 6 g/kg/day of ethanol in as little as three 1-hour access periods/day, which approximates the 24-hour intake of P rats with free-choice access to a single concentration of ethanol. The alcohol deprivation effect (ADE) is a transient increase in ethanol intake above baseline values upon re-exposure to ethanol access after an extended period of deprivation. The ADE has been proposed to be an animal model of relapse behavior, with the adult P rat displaying a robust ADE after prolonged abstinence. Overall, these findings indicate that the P rat can be effectively used in models assessing alcohol-preference, a genetic predisposition for alcohol abuse and/or alcoholism, and excessive drinking using protocols of binge-like or relapse-like drinking.
Keywords: alcoholism; Animal; Animals; Choice Behavior; Conditioning (Psychology); Disease Models; Ethanol; Food Preferences; Humans; Rats; Reinforcement (Psychology)

Alcohol-related genes: contributions from studies with genetically engineered mice - Crabbe, John C.; Phillips, Tamara J.; Harris, R. Adron; Arends, Michael A.; Koob, George F. (Addiction Biology, 2006)
Since 1996, nearly 100 genes have been studied for their effects related to ethanol in mice using genetic modifications including gene deletion, gene overexpression, gene knock-in, and occasionally by studying existing mutants. Nearly all such studies have concentrated on genes expressed in brain, and the targeted genes range widely in their function, including most of the principal neurotransmitter systems, several neurohormones, and a number of signaling molecules. We review 141 published reports of effects (or lack thereof) of 93 genes on responses to ethanol. While most studies have focused on ethanol self-administration and reward, and/or sedative effects, other responses studied include locomotor stimulation, anxiolytic effects, and neuroadaptation (tolerance, sensitization, withdrawal). About 1/4 of the engineered mutations increase self-administration, 1/3 decrease it, and about 40% have no significant effect. In many cases, the effects on self-administration are rather modest and/or depend on the specific experimental procedures. In some cases, genes in the background strains on which the mutant is placed are important for results. Not surprisingly, review of the systems affected further supports roles for serotonin, gamma-aminobutyric acid, opioids and dopamine, all of which have long been foci of alcohol research. Novel modulatory effects of protein kinase C and G protein-activated inwardly rectifying K+ (GIRK) channels are also suggested. Some newer research with cannabinoid systems is promising, and has led to ongoing clinical trials.
Keywords: alcoholism; Animal; Animals; Corticotropin-Releasing Hormone; Disease Models; dopamine; gamma-Aminobutyric Acid; Gene Expression; Genetic Engineering; Knockout; Mice; Opioid; Point Mutation; Receptors; Serotonin

Basis of the gabamimetic profile of ethanol - Breese, G. R.; Criswell, H. E.; Carta, M.; Dodson, P. D.; Hanchar, H. J.; Khisti, R. T.; Mameli, M.; Ming, Z.; Morrow, A. L.; Olsen, R. W.; Otis, T. S.; Parsons, L. H.; et al. (Alcoholism, Clinical and Experimental Research, 2006)
This article summarizes the proceedings of a symposium held at the 2005 Research Society on Alcoholism meeting. The initial presentation by Dr. Wallner provided evidence that selected GABA(A) receptors containing the delta subunit display sensitivity to low intoxicating ethanol concentrations and this sensitivity is further increased by a mutation in the cerebellar alpha6 subunit, found in alcohol-hypersensitive rats. Dr. Mameli reported that ethanol affects gamma-aminobutyric acid (GABA) function by affecting neural circuits that influence GABA release. Dr. Parsons presented data from electrophysiological and microdialysis investigations that ethanol is capable of releasing GABA from presynaptic terminals. Dr. Morrow demonstrated that systemic ethanol increases neuroactive steroids in brain, the absence of which alters various functional responses to ethanol. Dr. Criswell presented evidence that the ability of ethanol to increase GABA was apparent in some, but not all, brain regions indicative of regional specificity. Further, Dr. Criswell demonstrated that neurosteroids alone and when synthesized locally by ethanol act postsynaptically to enhance the effect of GABA released by ethanol in a region specific manner. Collectively, this series of reports support the GABAmimetic profile of acutely administered ethanol being dependent on several specific mechanisms distinct from a direct effect on the major synaptic isoforms of GABA(A) receptors.
Keywords: alcoholism; Amygdala; Anesthetics; Animals; Cerebellum; Ethanol; GABA-A; gamma-Aminobutyric Acid; Interneurons; Point Mutation; Progesterone; Rats; Receptors; Steroids

Behavioral and neurochemical interactions between Group 1 mGluR antagonists and ethanol: potential insight into their anti-addictive properties - Lominac, Kevin D.; Kapasova, Zuzana; Hannun, Reem A.; Patterson, Cole; Middaugh, Lawrence D.; Szumlinski, Karen K. (Drug and Alcohol Dependence, 2006)
Blockade of the mGluR5 subtype of Group 1 metabotropic glutamate receptor (mGluRs) reduces the rewarding effects of ethanol (EtOH), while the effects of mGluR1a blockade remain under-investigated. The present study compared the effects of pretreatment with the mGluR5 antagonist MPEP and the mGluR1a antagonist CPCCPOEt upon behavioral and neurochemical variables associated with EtOH reward in alcohol-preferring C57BL/6J mice. Pretreatment with either antagonist (0-10 mg/kg, IP) dose-dependently reduced measures of EtOH reward in an operant self-administration paradigm and the maximally effective antagonist dose (10 mg/kg) also blocked the expression of EtOH-induced place conditioning, as well as EtOH consumption under 24-h free-access conditions. MPEP pretreatment did not significantly alter the EtOH dose-locomotor response function; however, it prevented EtOH-induced changes in extracellular dopamine, glutamate and GABA in the nucleus accumbens (NAC). In contrast, CPCCOEt shifted the EtOH dose-response function downwards, enhanced the capacity of higher EtOH doses to elevate NAC levels of GABA and lowered extracellular dopamine and glutamate below baseline following EtOH injection. It is suggested that the "anti-alcohol" effects of MPEP may involve an attenuation of the neurochemical signals mediating EtOH reward, whereas those of CPCCOEt may involve an increased sensitivity to the inhibitory effects of EtOH upon brain and behavior.
Keywords: Alcohol Deterrents; alcoholism; Animals; Chromones; Classical; Conditioning; dopamine; Dose-Response Relationship; Drug; Ethanol; Excitatory Amino Acid Antagonists; gamma-Aminobutyric Acid; Glutamic Acid; Inbred C57BL; Male; Metabotropic Glutamate; Metabotropic Glutamate 5; Mice; Motor Activity; Nucleus Accumbens; Pyridines; Receptor; Receptors

Candidate genes and their regulatory elements: alcohol preference and tolerance - Saba, Laura; Bhave, Sanjiv V.; Grahame, Nicholas; Bice, Paula; Lapadat, Razvan; Belknap, John; Hoffman, Paula L.; Tabakoff, Boris (Mammalian Genome: Official Journal of the International Mammalian Genome Society, 2006)
QTL analysis of behavioral traits and mouse brain gene expression studies were combined to identify candidate genes involved in the traits of alcohol preference and acute functional alcohol tolerance. The systematic application of normalization and statistical analysis of differential gene expression, behavioral and expression QTL location, and informatics methodologies resulted in identification of 8 candidate genes for the trait of alcohol preference and 22 candidate genes for acute functional tolerance. Pathway analysis, combined with clustering by ontology, indicated the importance of transcriptional regulation and DNA and protein binding elements in the acute functional tolerance trait, and protein kinases and intracellular signal transduction elements in the alcohol preference trait. A rudimentary search for transcription control elements that could indicate coregulation of the panels of candidate genes produced modest results, implicating SMAD-3 in the regulation of four of the eight candidate genes for alcohol preference. However, the realization of the many caveats related to transcription factor binding site analysis, and attempts to correlate between transcription factor binding and function, forestalled any definitive global analysis of transcriptional control of differentially expressed candidate genes.
Keywords: Alcohol Drinking; Animals; Drug Tolerance; Genes; Inbred C57BL; Inbred DBA; Mice; Regulator; Signal Transduction

Chronic ethanol consumption increases dopamine uptake in the nucleus accumbens of high alcohol drinking rats - Carroll, Michelle R.; Rodd, Zachary A.; Murphy, James M.; Simon, Jay R. (Alcohol, 2006)
Past research has indicated that chronic ethanol exposure enhances dopamine (DA) neurotransmission in several brain regions. The present study examined the effects of chronic ethanol drinking on dopamine transporter (DAT) function in the nucleus accumbens (Acb) of High-Alcohol-Drinking replicate line 1 (HAD-1) rats. HAD rats were given concurrent 24-h access to 15% ethanol and water or water alone for 8 weeks. Subsequently, DA uptake and the Vmax of the DAT were compared between the two groups using homogenates of the nucleus accumbens. DA uptake was measured following a 2 min incubation at 37°C in the presence of 8 nM [3H]DA. For kinetic analyses, DA uptake was assessed in the presence of 5 concentrations of [3H]DA ranging from 8 nM to 500 nM. Analyses of the data revealed a significant increase in DA uptake in the ethanol group compared to water controls. Kinetic analyses revealed the change in DA uptake to be a consequence of an increase in the Vmax of transport. These findings demonstrate that chronic free-choice oral ethanol consumption in HAD-1 female rats increases DA uptake in the Acb by increasing the Vmax of the transporter. However, it is not known whether the ethanol-induced change in Vmax is caused by differences in the actual number of available transporter sites or from a difference in the velocity of operation of a similar number of transporters. Overall, the data indicate that chronic ethanol consumption by HAD-1 rats produces prolonged neuroadaptations within the mesolimbic DA system, which may be important for the understanding of the neurobiological basis of alcoholism.
Keywords: Dopamine transport; Dopamine uptake; Ethanol; High alcohol drinking rats

Coincident signaling in mesolimbic structures underlying alcohol reinforcement - Zhang, Tao A.; Maldve, Regina E.; Morrisett, Richard A. (Biochemical Pharmacology, 2006)
The medium spiny neurons (MSNs) of the nucleus accumbens function in a critical regard to examine and integrate information in the processing of rewarding behaviors. These neurons are aberrantly affected by drugs of abuse, including alcohol. However, ethanol is unlike any other common drug of abuse, due to its pleiotropic actions on intracellular and intercellular signaling processes. Intracellular biochemical pathways appear to critically contribute to long-term changes in the level of synaptic activation of these neurons, which have been implicated in ethanol dependence. Additionally, these neurons also display a fascinating pattern of up/down activity, which appears to be, at least in part, regulated by convergent activation of dopaminergic and glutamatergic (NMDA) inputs. Thus, dopaminergic and NMDA receptor-mediated synaptic transmission onto these neurons may constitute a critical site of ethanol action in mesolimbic structures. For instance, dopaminergic inputs alter the ability of ethanol to regulate NMDA receptor-mediated synaptic transmission onto accumbal MSNs. Prior activation of D1-signaling cascade through the cAMP-regulated phosphoprotein-32kD (DARPP-32) and protein phosphatase-1 (PP-1) pathway significantly attenuates ethanol inhibition of NMDA receptor function. Therefore, the interaction of D1-signaling and NMDA receptor signaling may alter NMDA receptor-dependent long-term synaptic plasticity, contributing to the development of ethanol-induced neuroadaptation of the reward pathway.
Keywords: alcoholism; Animals; Brain; Ethanol; N-Methyl-D-Aspartate; Neurons; Receptors; Reinforcement (Psychology); Synaptic Transmission

Daily patterns of ethanol drinking in peri-adolescent and adult alcohol-preferring (P) rats - Bell, Richard L.; Rodd, Zachary A.; Sable, Helen J. K.; Schultz, Jonathon A.; Hsu, Cathleen C.; Lumeng, Lawrence; Murphy, James M.; McBride, William J. (Pharmacology, Biochemistry, and Behavior, 2006)
Alcohol abuse among adolescents continues to be a major health problem for our society. Our laboratory has used the peri-adolescent alcohol-preferring, P, rat as an animal model of adolescent alcohol abuse. Even though peri-adolescent P rats consume more alcohol (g/kg/day) than their adult counterparts, it is uncertain whether their drinking is sufficiently aggregated to result in measurable blood ethanol concentrations (BECs). The objectives of this study were to examine daily alcohol drinking patterns of adolescent and adult, male and female P rats, and to determine whether alcohol drinking episodes were sufficiently aggregated to result in meaningful BECs. Male and female P rats were given 30 days of 24 h free-choice access to alcohol (15%, v/v) and water, with ad lib access to food, starting at the beginning of adolescence (PND 30) or adulthood (PND 90). Water and alcohol drinking patterns were monitored 22 h/day with a "lickometer" set-up. The results indicated that (a) peri-adolescent P rats consumed more water and total fluids than adult P rats, (b) female P rats consumed more water and total fluids than male P rats, (c) there were differences in alcohol, and water, licking patterns between peri-adolescent and adult and female and male P rats, (d) individual licking patterns revealed that alcohol was consumed in bouts often exceeding the amount required to self-administer 1 g/kg of alcohol, and (e) BECs at the end of the dark cycle, on the 30th day of alcohol access, averaged 50 mg%, with alcohol intakes during the last 1 to 2 h averaging 1.2 g/kg. Overall, these findings indicate that alcohol drinking patterns differ across the age and sex of P rats. This suggests that the effectiveness of treatments for reducing excessive alcohol intake may vary depending upon the age and/or sex of the subjects being tested.
Keywords: Aging; Alcohol Drinking; Animals; Body Weight; Circadian Rhythm; Drinking; Ethanol; Female; Male; Rats

delta-Subunit containing GABAA receptor knockout mice are less sensitive to the actions of 4,5,6,7-tetrahydroisoxazolo-[5,4-c]pyridin-3-ol - Boehm, Stephen L.; Homanics, Gregg E.; Blednov, Yuri A.; Harris, R. Adron (European Journal of Pharmacology, 2006)
The pharmacological profile of a gamma-aminobutyric acid A (GABA(A)) receptor depends upon subunit composition. Studies using recombinant expression systems suggest that delta-subunit containing GABA(A) receptors are particularly sensitive to the actions of the GABA(A) partial agonist, 4,5,6,7-tetrahydroisoxazolo-[5,4-c]pyridin-3-ol (THIP, gaboxadol). Here we investigated the actions of THIP in mutant mice lacking the GABA(A) receptor delta-subunit gene. Using the chloride flux assay, we determined that the actions of THIP were reduced by 21% in the cortical, but not cerebellar, membranes of knockout mice. Similar results were seen with another GABA(A) agonist, muscimol. Moreover, delta-subunit knockout mice exhibited a 54% reduction in sensitivity to the hypnotic actions of THIP as assessed by the loss of righting reflex test. These data support the notion that delta-containing GABA(A) receptors are at least partially responsible for the actions of THIP, and contribute to the growing literature suggesting that the pharmacological specificity of GABA(A) receptors depends on which subunits are present or absent.
Keywords: Animals; Cells; Cerebellum; Cerebral Cortex; Cultured; Female; GABA Agonists; GABA-A; Inbred C57BL; Isoxazoles; Knockout; Male; Mice; Muscimol; Receptors

Distribution of Corticotropin-releasing factor and Urocortin 1 in the vole brain - Lim, Miranda M.; Tsivkovskaia, Natalia O.; Bai, Yaohui; Young, Larry J.; Ryabinin, Andrey E. (Brain, behavior and evolution, 2006)
Brain receptor patterns for the corticotropin-releasing factor (CRF) receptors, CRF1 and CRF2, are dramatically different between monogamous and promiscuous vole species, and CRF physiologically regulates pair bonding behavior in the monogamous prairie vole. However, little is known whether species differences also exist in the neuroanatomical distribution of the endogenous ligands for the CRF1 and CRF2 receptors, such as CRF and urocortin-1 (Ucn1). We compared the expression of CRF and Ucn1 in four vole species, monogamous prairie and pine voles, and promiscuous meadow and montane voles, using in situ hybridization of CRF and Ucn1 mRNA. Our results reveal that CRF mRNA expression patterns in all four vole species appear highly conserved throughout the brain, including the olfactory bulb, nucleus accumbens, bed nucleus of the stria terminalis, medial preoptic area, central amygdala, hippocampus, posterior thalamus, and cerebellum. Similarly, Ucn1 mRNA primarily localized to the Edinger-Westphal nucleus in all four vole species. Immunocytochemistry in prairie and meadow voles confirmed localization of CRF and Ucn1 protein to these previously identified brain regions. These data demonstrate a striking dichotomy between the extraordinary species diversity of brain receptor patterns when compared to the highly conserved brain distributions of their respective ligands. Our findings generate novel hypotheses regarding the evolutionary mechanisms underlying the neural circuitry of species-typical social behaviors.

DNA microarray and proteomic strategies for understanding alcohol action - Sikela, James M.; Maclaren, Erik J.; Kim, Young; Karimpour-Fard, Anis; Cai, Wei-Wen; Pollack, Jonathan; Hitzemann, Robert; Belknap, John; McWeeney, Shannon; Kerns, Robnet T.; Downing, Chris; Johnson, Thomas E.; et al. (Alcoholism, Clinical and Experimental Research, 2006)
This article summarizes the proceedings of a symposium presented at the 2005 annual meeting of the Research Society on Alcoholism in Santa Barbara, California. The organizer was James M. Sikela, and he and Michael F. Miles were chairs. The presentations were (1) Genomewide Surveys of Gene Copy Number Variation in Human and Mouse: Implications for the Genetics of Alcohol Action, by James M. Sikela; (2) Regional Differences in the Regulation of Brain Gene Expression: Relevance to the Detection of Genes Associated with Alcohol-Related Traits, by Robert Hitzemann; (3) Identification of Ethanol Quantitative Trait Loci Candidate Genes by Expression Profiling in Inbred Long Sleep/Inbred Short Sleep Congenic Mice, by Robnet T. Kerns; and (4) Quantitative Proteomic Analysis of AC7-Modified Mice, by Kathleen J. Grant.
Keywords: alcoholism; Animals; Environment; Ethanol; Female; Gene Expression Profiling; Humans; Male; Mice; Oligonucleotide Array Sequence Analysis; Proteomics; Quantitative Trait Loci; Sleep; Species Specificity

Effects of chronic alcohol and repeated deprivations on dopamine D1 and D2 receptor levels in the extended amygdala of inbred alcohol-preferring rats - Sari, Youssef; Bell, Richard L.; Zhou, Feng C. (Alcoholism, Clinical and Experimental Research, 2006)
BACKGROUND: Dopaminergic (DA) activity in the extended amygdala (EA) has been known to play a pivotal role in mediating drug and alcohol addiction. Alterations of DA activity within the EA after chronic exposure to alcohol or substances of abuse are considered a major mechanism for the development of alcoholism and addiction. To date, it is not clear how different patterns of chronic alcohol drinking affect DA receptor levels. Therefore, the current studies investigated the effects of chronic ethanol consumption, with or without deprivations, on D1 and D2 receptor densities within the EA. METHODS: Inbred alcohol-preferring (iP) rats were divided into 3 groups with the following treatments: (1) water for 14 weeks; (2) continuous alcohol (C-Alc) for 14 weeks [24-hour concurrent access to 15 and 30% (v/v) ethanol]; or (3) repeatedly deprived of alcohol (RD-Alc) (24-hour concurrent access to 15 and 30% ethanol for 6 weeks, followed by 2 cycles of 2 weeks of deprivation of and 2 weeks of reexposure to ethanol access). At the end of 14 weeks, the rats were killed for autoradiographic labeling of D1 and D2 receptors. RESULTS: Compared with the water control group, both the C-Alc and the RD-Alc groups displayed increases in D1 receptor binding density in the anterior region of the Acb core, whereas the RD-Alc group displayed additional increases in D1 receptor binding density in anterior regions of the lateral and intercalated nuclei of the amygdala. Additionally, both C-Alc and RD-Alc rats displayed increases in D2 receptor binding density in anterior regions of the Acb shell and core, whereas RD-Alc rats displayed additional increases in D2 receptor binding density in the dorsal striatum. CONCLUSION: The results of this study indicate that 14-week extended alcohol drinking with continuous chronic or repeated deprivations increase binding sites of D1 and D2 receptors in specific regions of the EA with greater sensitivity in the anterior regions. The repeated deprivation has greater effect on altering D1 and D2 receptor binding sites in the Acb, dorsal striatum, and subamygdala regions. The current result indicates that the two drinking paradigms may have common as well as differential mechanisms on alteration of dopamine receptor-binding sites in specific regions of the EA.
Keywords: alcoholism; Amygdala; Animals; Autoradiography; Brain Mapping; Dopamine D1; Dopamine D2; Ethanol; Inbred Strains; Male; Nucleus Accumbens; Rats; Receptors; Reward; Substance Withdrawal Syndrome; Ventral tegmental area

Effects of genetic and procedural variation on measurement of alcohol sensitivity in mouse inbred strains - Crabbe, John C.; Metten, Pamela; Ponomarev, Igor; Prescott, Carol A.; Wahlsten, Douglas (Behavior Genetics, 2006)
Mice from eight inbred strains were studied for their acute sensitivity to ethanol as indexed by the degree of hypothermia (HT), indexed as the reduction from pre-injection baseline of their body temperature. Two weeks later, mice were tested for their loss of righting reflex (LRR) after a higher dose of ethanol. The LRR was tested using the "classical" method of watching for recovery in animals placed on their backs in a V-shaped trough and recording duration of LRR. In a separate test, naive animals of the same strains were tested for HT repeatedly to assess the development of rapid (RTOL) and chronic tolerance (CTOL). We have recently developed a new method for testing LRR that leads to a substantial increase in the sensitivity of the test. Strains also have been found to differ in the new LRR test, as well as in the development of acute functional tolerance (AFT) to this response. In addition, our laboratory has periodically published strain difference data on the older versions of the HT and LRR responses. The earlier tests used some of the exact substrains tested currently, while for some strains, different substrains (usually, Nih versus Jax) were tested. We examined correlations of strain means to see whether patterns of strain differences were stable across time and across different test variants assessing the same behavioral construct. HT strain sensitivity scores were generally highly correlated across a 10-23 years period and test variants. The CTOL to HT was well-correlated across studies, and was also genetically similar to RTOL. The AFT, however, was related to neither RTOL nor CTOL, although this may be because different phenotypic end points were compared. The LRR data, which included a variant of the classical test, were not as stable. Measures of LRR onset were reasonably well correlated, as were those taken at recovery (e.g., duration). However, the two types of measures of LRR sensitivity to ethanol appear to be tapping traits that differ genetically. Also, the pattern of genetic correlation between HT and LRR initially reported in 1983 was not seen in current and contemporaneous studies. In certain instances, substrain seems to matter little, while in others, substrains differed a great deal. These data are generally encouraging about the stability of genetic differences.
Keywords: alcoholism; Animals; Brain; Ethanol; Female; Genetic Predisposition to Disease; Hypnotics and Sedatives; Hypothermia; Inbred A; Inbred C3H; Inbred C57BL; Inbred DBA; Inbred Strains; Male; Mice; Motor Activity; Reflex; Species Specificity

Ethanol enhancement of cocaine- and amphetamine-regulated transcript mRNA and peptide expression in the nucleus accumbens - Salinas, Armando; Wilde, Jennifer D.; Maldve, Regina E. (Journal of Neurochemistry, 2006)
Cocaine- and amphetamine-regulated transcript (CART) is a peptide neurotransmitter that has been implicated in drug reward and reinforcement. CART mRNA and peptide expression are highly concentrated in several compartments of the mesolimbic reward pathway. Several lines of evidence suggest that CART peptides may contribute to rewarding behaviors and the addiction liability of psychostimulants; however, there are no reports of basic work concerning CART in relation to alcohol and mechanisms of alcohol dependence development. Therefore, in this study we investigated the response of CART transcript and peptide to acute ethanol administration in vivo. Rats were administered ethanol (1 g/kg or 3.5 g/kg, 1 h, ip) and CART expression was measured by RT-PCR in the nucleus accumbens (NAcc). Ethanol (3.5 g/kg) increased CART transcription markedly. The interactions of dopamine on ethanol-induced CART expression were further evaluated pharmacologically using D1 and D2/D3 receptor antagonists. Both SCH 23390 (0.25 mg/kg) or raclopride (0.2 mg/kg) pre-treatment significantly suppressed ethanol-enhancement of CART mRNA transcription. Confocal immunofluorescence microscopy revealed that CART peptide immunoreactivity was also enhanced in both the core and the shell of the NAcc by ethanol administration. These findings demonstrate that CART mRNA and peptide expression are responsive to acute ethanol administrated in vivo and suggests that CART peptides may be important in regulating the rewarding and reinforcing properties of ethanol.
Keywords: Analysis of Variance; Animals; Benzazepines; Blotting; Central Nervous System Depressants; Dopamine Antagonists; Dose-Response Relationship; Drug; Drug Interactions; Ethanol; gamma-Aminobutyric Acid; Gene Expression; Male; Messenger; Nerve Tissue Proteins; Northern; Nucleus Accumbens; Raclopride; Rats; Reverse Transcriptase Polymerase Chain Reaction; RNA; Sprague-Dawley

From blue states to up states: a regional view of NMDA-ethanol interactions - Woodward, John J.; Ron, Dorit; Winder, Danny; Roberto, Marisa (Alcoholism, Clinical and Experimental Research, 2006)
This article summarizes the proceedings of a symposium at the 2005 Research Society on Alcoholism Meeting in Santa Barbara, California, organized and cochaired by John J. Woodward and Dorit Ron. The purpose of the symposium was to discuss recent findings that extend our understanding of the importance of the N-methyl-D-aspartate (NMDA) receptor as a target for ethanol action in the brain. These receptors are ligand-gated ion channels that are activated by the neurotransmitter glutamate and are critically involved in many forms of synaptic plasticity including those associated with learning and memory. In the first presentation, Dorit Ron presented data showing how activation of Fyn or Src tyrosine kinases differentially regulated the cell surface expression and activity of NR2A and NR2B containing NMDA receptors. Danny Winder discussed the effects of ethanol on NMDA receptor-dependent long-term potentiation in the bed nucleus of the stria terminalis (BNST), a brain region associated with the interaction between stress and drug/alcohol use. In the third presentation, Marisa Roberto described adaptations in the expression and function of NMDA receptors in the central nucleus of the amygdala following chronic exposure to ethanol. Finally, John Woodward described the effects of ethanol on the activity of neurons in deep layers of the prefrontal cortex using a novel slice coculture preparation.
Keywords: alcoholism; Amygdala; Animals; Brain; Drug Tolerance; Ethanol; Glutamic Acid; Humans; Long-Term Potentiation; N-Methyl-D-Aspartate; Neuronal Plasticity; Prefrontal Cortex; Psychological; Receptors; Septal Nuclei; Stress; Substance-Related Disorders; Synapses; Tissue Culture Techniques

From gene to behavior and back again: new perspectives on GABAA receptor subunit selectivity of alcohol actions - Boehm, Stephen L.; Ponomarev, Igor; Blednov, Yuri A.; Harris, R. Adron (Advances in Pharmacology (San Diego, Calif.), 2006)
gamma-Aminobutyric acid A (GABA(A)) receptors are believed to mediate a number of alcohol's behavioral actions. Because the subunit composition of GABA(A) receptors determines receptor pharmacology, behavioral sensitivity to alcohol (ethanol) may depend on which subunits are present (or absent). A number of knockout and/or transgenic mouse models have been developed (alpha1, alpha2, alpha5, alpha6, beta2, beta3, gamma2S, gamma2L, delta) and tested for behavioral sensitivity to ethanol. Here we review the current GABA(A) receptor subunit knockout and transgenic literature for ethanol sensitivity, and integrate these results into those obtained using quantitative trait loci (QTL) analysis and gene expression assays. Converging evidence from these three approaches support the notion that different behavioral actions of ethanol are mediated by specific subunits, and suggest that new drugs that target specific GABA(A subunits may selectively alter some behavioral actions of ethanol without altering others. Current data sets provide stronge)st evidence for a role of alpha1 subunits in ethanol-induced loss of righting reflex and alpha5 subunits in ethanol-stimulated locomotion. Nevertheless, three-way validation is hampered by the incomplete behavioral characterization of many of the mutant mice, and additional subunits are likely to be linked to alcohol actions as behavioral testing progresses.

Gamma-aminobutyric acid type A receptors and alcoholism: intoxication, dependence, vulnerability, and treatment - Krystal, John H.; Staley, Julie; Mason, Graeme; Petrakis, Ismene L.; Kaufman, Joan; Harris, R. Adron; Gelernter, Joel; Lappalainen, Jaakko (Archives of General Psychiatry, 2006)
CONTEXT: Alcohol facilitates gamma-aminobutyric acid (GABA) function, and GABA type A (GABA(A)) receptor-facilitating agents suppress alcohol withdrawal symptoms. Advances in molecular neuroscience, genetics, and neuroimaging provide new insights into the role of brain GABA systems in short- and long-term alcohol effects. OBJECTIVE: To review the role of brain GABA systems in alcohol response, alcohol dependence, alcoholism vulnerability, and alcoholism pharmacotherapy. DESIGN: Literature review. RESULTS: Alcohol increases GABA release, raises neurosteroid levels, and may potently enhance the function of a GABA(A) receptor subclass that shows high affinity for GABA and neurosteroids, relative insensitivity to benzodiazepines, low chloride conductance, and an extrasynaptic location. Variation in GABA(A) receptor subunit genes may contribute to the vulnerability to alcoholism, particularly in the context of environmental risk factors. Alcohol dependence is associated with time-dependent changes in brain GABA(A) receptor density and subunit gene expression levels that contribute to a withdrawal-related deficit in GABA(A) receptor function. However, cortical GABA levels are not reduced during acute withdrawal. Benzodiazepine-assisted detoxification enhances a phasic component of GABA function. However, novel treatments target the tonic component of GABA neurotransmission mediated by benzodiazepine-insensitive GABA(A) receptors. Smoking attenuates withdrawal-related disturbances in brain GABA function, perhaps contributing to comorbid nicotine and alcohol dependence. The GABA systems show recovery with long-term sobriety. CONCLUSIONS: Recent research deepens our understanding of the role of GABA systems in alcohol action, alcohol dependence, and the vulnerability to alcoholism. Also, GABA(A) receptor subtype-selective treatments merit exploration for reducing withdrawal symptoms and drinking in alcohol-dependent individuals.
Keywords: alcoholism; Benzodiazepines; Brain; Cerebral Cortex; GABA-A; gamma-Aminobutyric Acid; Gene Expression; Genetic Predisposition to Disease; Humans; Receptors; Risk Factors; Substance Withdrawal Syndrome

Gene array profiles of alcohol and aldehyde metabolizing enzymes in brains of C57BL/6 and DBA/2 mice - Bhave, Sanjiv V.; Hoffman, Paula L.; Lassen, Natalie; Vasiliou, Vasilis; Saba, Laura; Deitrich, Richard A.; Tabakoff, Boris (Alcoholism, Clinical and Experimental Research, 2006)
BACKGROUND: Differences in ethanol metabolizing enzymes expressed in brain have been suggested to contribute to the significant differences in ethanol (alcohol) preference between inbred C57BL/6 and DBA/2 mouse strains. METHODS: We have utilized 2 different platforms of oligonucleotide microarray technology (CodeLink UniSet I BioArray from G.E. Healthcare and MG U74A v2.0 from Affymetrix) to simultaneously assess expression of alcohol and acetaldehyde metabolizing enzymes in the whole brain of naïve (no exposure to alcohol) C57BL/6 and DBA/2 mice. RESULTS: There were no significant differences between the 2 strains of mice in gene expression intensity for alcohol dehydrogenases (ADH), catalase, and a number of the cytochrome P450 family of genes, which can be involved in ethanol catabolism. However, significantly higher expression of mRNA for aldehyde dehydrogenase 2 (ALDH2), an isoform mainly responsible for the catabolism of acetaldehyde, was observed in whole brains of DBA/2 mice with both platforms. Aldehyde dehydrogenase 2 protein was also higher in DBA/2 brain. Expression of aldehyde dehydrogenase 1A1 (ALDH1A1) mRNA was found to be higher in brains of DBA/2 mice, when measured with the CodeLink platform, but not when measured with Affymetrix arrays or quantitative reverse transcriptase-real-time polymerase chain reaction (qRT-PCR). The ALDH1A1 protein, however, reflected the results obtained with the CodeLink arrays and was higher in DBA/2 brain, compared with brains of C57BL/6 mice. In contrast, the expression intensity for the aldehyde dehydrogenase 7A1 (ALDH7A1) mRNA and protein was significantly higher in C57BL/6 mice than DBA/2 mice. These expression differences are consistent with more rapid metabolism of acetaldehyde in brains of DBA/2 mice. CONCLUSIONS: The use of 2 different microarray platforms provides important cross-validation of many results, and some discrepancies can be resolved with qRT-PCR and immunoblotting. The expression differences that were validated may affect alcohol/aldehyde metabolism in brain and/or alcohol preference in the 2 strains of mice.
Keywords: Acetaldehyde; Alcohol Dehydrogenase; Aldehyde Dehydrogenase; Aldehydes; Animals; Brain; Catalase; Central Nervous System Depressants; Cytochrome P-450 Enzyme System; Enzymologic; Ethanol; Gene Expression Profiling; Gene Expression Regulation; Inbred C57BL; Inbred DBA; Male; Messenger; Mice; Mitochondrial; Oligonucleotide Array Sequence Analysis; RNA

Genetic independence of mouse measures of some aspects of novelty seeking - Kliethermes, Christopher L.; Crabbe, John C. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
High novelty seeking is a complex personality attribute correlated with risk for substance abuse. There are many putative mouse models of some aspects of novelty seeking, but little is known of genetic similarities among these models. To assess the genetic coherence of “novelty seeking,” we compared the performance of 14 inbred strains of mice in five tests: activity in a novel environment, novel environment preference, head dipping on a hole-board, object preference, and a two-trial version of the spontaneous alternation task. Differences among strains were observed for all tasks, but performance in any given task was generally not predictive of performance in any other. To evaluate similarities among these tasks further, we selectively bred lines of mice for high or low head dipping on the hole-board. Similar to results from the inbred strain experiments, head dipping was not correlated with performance in the other measures but was genetically correlated with differences in locomotor activity. Using two approaches to estimating common genetic influences across tasks, we have found little evidence that these partial models of novelty seeking reflect the influence of common genes or measure a single, unified construct called novelty seeking. Based on the substantial influence of genetic factors, ease of implementation, and relative independence from general locomotion, head dipping on a hole-board is a good task to use in the domain of novelty seeking, but multiple tasks, including others not tested here, would be needed to capture the full genetic range of the behavioral domain.
Keywords: drug abuse; Inbred Strains

Glutamate and dopamine synaptic terminals in extended amygdala after 14-week chronic alcohol drinking in inbred alcohol-preferring rats - Zhou, Feng C.; Sahr, Robert N.; Sari, Youssef; Behbahani, Kamran (Alcohol (Fayetteville, N.Y.), 2006)
Alcohol has been shown to affect glutamate (GLU) and dopamine (DA) release and their correlated receptors in the key reward center–extended amygdala–which includes the shell of nucleus accumbens (sNAc) and central nucleus of amygdala (cAmg). It is unclear to date whether there is an alteration in the number of presynaptic GLU/DA nerve terminals. In this study, we investigated the number of GLU and DA terminals in the extended amygdala of alcohol-preferring (P) rats that chronically drank ethanol. P rats have a propensity to drink ethanol to intoxication and develop an alcohol dependency. The P rats were divided into (1) Water group given ad libitum chow and water for 14 weeks; (2) Continuous alcohol group (C-Alc) given ad libitum chow and choice of 15 or 30% (v/v) ethanol or water for 14 weeks; and (3) Repeated deprivation (RD-Alc) group given the same choice of ethanol or water for 6 weeks, followed by a twice repeated cycle of 2 weeks without ethanol followed by 2 weeks with ethanol. Two subpopulations of GLU terminals were labeled by immunostaining for the vesicular GLU transporter 1 (vGLUT1) and vesicular GLU transporter 2 (vGLUT2). DA terminals were labeled by immunostaining for tyrosine hydroxylase (TH). The GLU and DA immunostained (im) varicosities were quantified and analyzed using stereological methods. We found that chronic alcohol did not alter the number of TH-im terminals in the extended amygdala in either the C-Alc or RD-Alc drinking paradigms. Thus, the increases in extracellular levels of DA previously reported following chronic alcohol are likely due to a change in the efficiency of DA release rather than a change in the number of DA terminals. The number of vGLUT1-im terminals was also unchanged in the extended amygdala; however, the number of vGLUT2-im terminals, which represent the greater population of GLU terminals, was increased in the sNAc of the RD-Alc group compared to the Water group. Chronic alcohol is known to affect GLU release, and our findings indicate that repeated alcohol deprivation may preferentially increase GLU terminals in the sNAc bearing the vGLUT2, which are primarily afferents from the thalamus. Our results further indicate that repeated deprivation of alcohol can change the ratio of GLU to DA innervation in the sNAc, a key region of the reward circuitry.
Keywords: Alcohol Drinking; Amygdala; Animals; dopamine; glutamate; Inbred Strains; Male; Neuronal Plasticity; Presynaptic Terminals; Rats; Receptors

Homer proteins: implications for neuropsychiatric disorders - Szumlinski, Karen K; Kalivas, Peter W; Worley, Paul F (Signalling mechanisms, 2006)
Homer proteins regulate signal transduction, synaptogenesis and receptor trafficking, in addition to maintaining and regulating extracellular glutamate levels in limbo–corticostriatal brain regions. Converging preclinical observations indicate a potential role for both immediate early gene Homer isoforms and constitutively expressed Homer isoforms in behavioral pathologies associated with neuropsychiatric disorders, such as addiction and/or alcoholism, depression, anxiety, epilepsy and schizophrenia.

Impact of sex: determination of alcohol neuroadaptation and reinforcement - Wiren, Kristine M.; Hashimoto, Joel G.; Alele, Paul E.; Devaud, Leslie L.; Price, Kimber L.; Middaugh, Lawrence D.; Grant, Kathleen A.; Finn, Deborah A. (Alcoholism, Clinical and Experimental Research, 2006)
This article represents the proceedings of a symposium at the Research Society on Alcoholism meeting in Santa Barbara, California. The organizers/chairs were Kristine M. Wiren and Deborah A. Finn. Following a brief introduction by Deborah Finn, the presentations were (1) The Importance of Gender in Determining Expression Differences in Mouse Lines Selected for Chronic Ethanol Withdrawal Severity, by Kristine M. Wiren and Joel G. Hashimoto; (2) Sex Differences in Ethanol Withdrawal Involve GABAergic and Stress Systems, by Paul E. Alele and Leslie L. Devaud; (3) The Influence of Sex on Ethanol Consumption and Reward in C57BL/6 Mice, by Kimber L. Price and Lawrence D. Middaugh; and (4) Sex Differences in Alcohol Self-administration in Cynomolgus Monkeys, by Kathleen A. Grant.
Keywords: Adaptation; Alcohol Withdrawal Delirium; alcoholism; Animals; Brain; Brain Mapping; Ethanol; Gene Expression; Genetic; Genotype; Humans; Inbred Strains; Mice; Neurons; Physiological; Reinforcement (Psychology); Selection; Sex Factors; Species Specificity

In Vivo Quantification of Ethanol Kinetics in Rat Brain - Adalsteinsson, Elfar; Sullivan, Edith V.; Mayer, Dirk; Pfefferbaum, Adolf (Neuropsychopharmacology, 2006)
Proton magnetic resonance spectroscopy was used at 3T to measure the uptake and clearance of brain ethanol in rats after bolus intraperitoneal (i.p.) or intragastric (i.g.) alcohol injection, and to estimate the effects of acute alcohol on brain metabolites. The observation duration was 1|[ndash]|1.5|[thinsp]\textbarh with temporal resolution of alcohol sampling ranging from 4|[thinsp]\textbars|[ndash]|4|[thinsp]\textbarmin. The observed time course of alcohol brain concentration followed a consistent pattern characterized by a rapid absorption, an intermediate distribution, and a slower clearance that approached a linear decay. In a sample of eight healthy Wistar rats, the intercept of the linear clearance term, extrapolated back to the time of injection, correlated well with the administered dose per unit of lean body mass. Alcohol concentration estimation based on spectroscopically measured clearance was compared with blood alcohol levels from blood samples at the end of observation, and were in good agreement with the administered dose. Serial proton spectroscopy measurements provide a valid in vivo method for quantifying brain alcohol uptake and elimination kinetics in real time.
Keywords: alcohol; Ethanol; glutamate; imaging; MR spectroscopy; rat

Kappa-opioid receptor modulation of accumbal dopamine concentration during operant ethanol self-administration - Doyon, William M.; Howard, Elaina C.; Shippenberg, Toni S.; Gonzales, Rueben A. (Neuropharmacology, 2006)
Our study examined ethanol self-administration and accumbal dopamine concentration during kappa-opioid receptor (KOPr) blockade. Long-Evans rats were trained to respond for 20 min of access to 10% ethanol (with sucrose) over 7 days. Rats were injected s.c. with the long-acting KOPr antagonist, nor-binaltorphimine (NOR-BNI; 0 or 20 mg/kg) 15-20 h prior to testing. Microdialysis revealed a transient elevation in dopamine concentration within 5 min of ethanol access in controls. NOR-BNI-treated rats did not exhibit this response, but showed a latent increase in dopamine concentration at the end of the access period. The rise in dopamine levels correlated positively with dialysate ethanol concentration but not in controls. NOR-BNI did not alter dopamine levels in rats self-administering 10% sucrose. The transient dopamine response during ethanol acquisition in controls is consistent with previous results that were attributed to ethanol stimulus cues. The altered dopamine response to NOR-BNI during ethanol drinking suggests that KOPr blockade temporarily uncovered a pharmacological stimulation of dopamine release by ethanol. Despite these neurochemical changes, NOR-BNI did not alter operant responding or ethanol intake, suggesting that the KOPr is not involved in ethanol-reinforced behavior under the limited conditions we studied.
Keywords: (trans)-Isomer; 3; 4-Dichloro-N-methyl-N-(2-(1-pyrrolidinyl)-cyclohexyl)-benzeneacetamide; Analgesics; Animal; Animals; Area Under Curve; Behavior; Central Nervous System Depressants; Conditioning; dopamine; Dose-Response Relationship; Drinking Behavior; Drug; Drug Interactions; Ethanol; kappa; Long-Evans; Male; Microdialysis; Naltrexone; Narcotic Antagonists; Non-Narcotic; Nucleus Accumbens; Operant; Opioid; Rats; Receptors; Self Administration

Knockin mice with ethanol-insensitive alpha1-containing gamma-aminobutyric acid type A receptors display selective alterations in behavioral responses to ethanol - Werner, David F.; Blednov, Yuri A.; Ariwodola, Olusegun J.; Silberman, Yuval; Logan, Exazevia; Berry, Raymond B.; Borghese, Cecilia M.; Matthews, Douglas B.; Weiner, Jeffrey L.; Harrison, Neil L.; Harris, R. Adron; Homanics, Gregg E. (The Journal of Pharmacology and Experimental Therapeutics, 2006)
Despite the pervasiveness of alcohol (ethanol) use, it is unclear how the multiple molecular targets for ethanol contribute to its many behavioral effects. The function of GABA type A receptors (GABA(A)-Rs) is altered by ethanol, but there are multiple subtypes of these receptors, and thus far, individual subunits have not been definitively linked with specific behavioral actions. The alpha1 subunit of the GABA(A)-R is the most abundant alpha subunit in the brain, and the goal of this study was to determine the role of receptors containing this subunit in alcohol action. We designed an alpha1 subunit with serine 270 to histidine and leucine 277 to alanine mutations that was insensitive to potentiation by ethanol yet retained normal GABA sensitivity and constructed knockin mice containing this mutant subunit. Hippocampal slice recordings from these mice indicated that the mutant receptors were less sensitive to ethanol's potentiating effects. Behaviorally, we observed that mutant mice recovered more quickly from the motor-impairing effects of ethanol and etomidate, but not pentobarbital, and showed increased anxiolytic effects of ethanol. No differences were observed in ethanol-induced hypnosis, locomotor stimulation, cognitive impairment, or in ethanol preference and consumption. Overall, these studies demonstrate that the postsynaptic effects of ethanol at GABAergic synapses containing the alpha1 subunit are important for specific ethanol-induced behavioral effects.
Keywords: Animal; Animals; Behavior; Body Temperature; Ethanol; Etomidate; Female; GABA-A; Hippocampus; Inbred C57BL; Male; Maze Learning; Mice; Motor Activity; Quinine; Receptors; Reflex; Saccharin; Structure-Activity Relationship

Longitudinal brain magnetic resonance imaging study of the alcohol-preferring rat. Part II: effects of voluntary chronic alcohol consumption - Pfefferbaum, Adolf; Adalsteinsson, Elfar; Sood, Rohit; Mayer, Dirk; Bell, Richard; McBride, William; Li, Ting-Kai; Sullivan, Edith V. (Alcoholism, Clinical and Experimental Research, 2006)
BACKGROUND: Tracking the dynamic course of human alcoholism brain pathology can be accomplished only through naturalistic study and without opportunity for experimental manipulation. Development of an animal model of alcohol-induced brain damage, in which animals consume large amounts of alcohol following cycles of alcohol access and deprivation and are examined regularly with neuroimaging methods, would enable hypothesis testing focused on the degree, nature, and factors resulting in alcohol-induced brain damage and the prospects for recovery or relapse. METHODS: We report the results of longitudinal magnetic resonance imaging (MRI) studies of the effects of free-choice chronic alcohol intake on the brains of 2 cohorts of selectively bred alcohol-preferring (P) rats. In the companion paper, we described the MRI acquisition and analysis methods, delineation of brain regions, and growth patterns in total brain and selective structures of the control rats in the present study. Both cohorts were studied as adults for about 1 year and consumed high doses of alcohol for most of the study duration. The paradigm involved a 3-bottle choice with 0, 15 (or 20%), and 30% (or 40%) alcohol available in several different exposure schemes: continuous exposure, cycles of 2 weeks on followed by 2 weeks off alcohol, and binge drinking in the dark. RESULTS: Brain structures of the adult P rats in both the alcohol-exposed and the water control conditions showed significant growth, which was attenuated in a few measures in the alcohol-exposed groups. The region with the greatest demonstrable effect was the corpus callosum, measured on midsagittal images. CONCLUSION: The P rats showed an age-alcohol interaction different from humans, in that normal growth in selective brain regions that continues in adult rats was retarded.
Keywords: Animals; Brain; Corpus Callosum; Ethanol; Longitudinal Studies; Magnetic Resonance Imaging; Male; Rats; Time Factors

Longitudinal brain magnetic resonance imaging study of the alcohol-preferring rat. Part I: adult brain growth - Sullivan, Edith V.; Adalsteinsson, Elfar; Sood, Rohit; Mayer, Dirk; Bell, Richard; McBride, William; Li, Ting-Kai; Pfefferbaum, Adolf (Alcoholism, Clinical and Experimental Research, 2006)
BACKGROUND: The alcohol-preferring (P) rat, a Wistar strain selectively bred to consume large amounts of alcohol voluntarily, has been used as an animal model of human alcoholism for 3 decades. Heretofore, knowledge about brain morphology has been confined to postmortem examination. Quantitative neuroimaging procedures make it feasible to examine the potential longitudinal effects of alcohol exposure in vivo, while controlling modifying factors, such as age, nutrition, and exercise. To date, few imaging studies have considered what morphological changes occur with age in the rodent brain, and none has systematically applied quantitative neuroimaging approaches to measure volume changes in regional brain structures over extended periods in the adult rat. METHODS: We used structural magnetic resonance imaging (MRI) in a longitudinal design to examine 2 cohorts of adult P rats, never exposed to alcohol: Cohort A included 8 rats, 7 of which survived the entire study (578 days) and 4 MRI sessions; Cohort B included 9 rats, all of which survived the study (452 days) and 5 MRI sessions. RESULTS: Growth in whole-brain volume reached maximal levels by about 450 days of age, whereas body weight continued its gain without asymptote. Growth was not uniform across the brain structures measured. Over the initial 12 months of the study, the corpus callosum area expanded 36%, cerebellum 17%, and hippocampus 10%, whereas ventricle size was unchanged. Factors affecting growth rate estimates included litter effects, MR image signal-to-noise ratio, and measurement error. CONCLUSION: Unlike longitudinal human reports of regional volume declines in aging brain tissue, several brain structures in adult rats continued growing, and some growth patterns were litter-dependent. Determining normal regional growth patterns of brain and of the substantial variance exerted by litter differences, even in selectively bred rats, is essential for establishing baselines against which normal and aberrant dynamic changes can be detected in animal models of aging and disease.
Keywords: Aging; alcoholism; Animal; Animals; Brain; Disease Models; Ethanol; Longitudinal Studies; Magnetic Resonance Imaging; Male; Rats

Neuroadaptations of Cdk5 in cholinergic interneurons of the nucleus accumbens and prefrontal cortex of inbred alcohol-preferring rats following voluntary alcohol drinking - Camp, Marguerite Charlotte; Mayfield, Roy Dayne; McCracken, Mandy; McCracken, Lindsay; Alcantara, Adriana Angelica (Alcoholism, Clinical and Experimental Research, 2006)
BACKGROUND: Neurobiological studies have identified brain areas and related molecular mechanisms involved in alcohol abuse and dependence. Specific cell types in these brain areas and their role in alcohol-related behaviors, however, have not yet been identified. This study examined the involvement of cholinergic cells in inbred alcohol-preferring rats following 1 month of alcohol drinking. Cyclin-dependent kinase 5 (Cdk5) immunoreactivity (IR), a marker of neuronal plasticity, was examined in cholinergic neurons of the nucleus accumbens (NuAcc) and prefrontal cortex (PFC) and other brain areas implicated in alcohol drinking, using dual immunocytochemical (ICC) procedures. Single Cdk5 IR was also examined in several brain areas implicated in alcohol drinking. METHODS: The experimental group self-administered alcohol using a 2-bottle-choice test paradigm with unlimited access to 10% (v/v) alcohol and water for 23 h/d for 1 month. An average of 6 g/kg alcohol was consumed daily. Control animals received identical treatment, except that both bottles contained water. Rats were perfused and brain sections were processed for ICC procedures. RESULTS: Alcohol drinking resulted in a 51% increase in Cdk5 IR cholinergic interneurons in the shell NuAcc, while in the PFC there was a 51% decrease in the percent of Cdk5 IR cholinergic interneurons in the infralimbic region and a 46% decrease in Cdk5 IR cholinergic interneurons in the prelimbic region. Additionally, single Cdk5 IR revealed a 42% increase in the central nucleus of the amygdala (CNA). CONCLUSIONS: This study identified Cdk5 neuroadaptation in cholinergic interneurons of the NuAcc and PFC and in other neurons of the CNA following 1 month of alcohol drinking. These findings contribute to our understanding of the cellular and molecular basis of alcohol drinking and toward the development of improved region and cell-specific pharmacotherapeutic and behavioral treatment programs for alcohol abuse and alcoholism.
Keywords: Adaptation; Alcohol Drinking; Animals; Choice Behavior; Cholinergic Fibers; Cyclin-Dependent Kinase 5; Ethanol; Female; Interneurons; Nucleus Accumbens; Physiological; Prefrontal Cortex; Rats; Wistar

Nociceptin/orphanin FQ presynaptically decreases GABAergic transmission and blocks the ethanol-induced increase of GABA release in central amygdala - Roberto, Marisa; Siggins, George R. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
Behavioral studies show that the GABAergic system in the central amygdala (CeA) nucleus has a complex role in the reinforcing effects effects of ethanol and the anxiogenic response to ethanol withdrawal. Opioid peptides and nociceptin/orphanin FQ (nociceptin) within the CeA are implicated also in regulating voluntary ethanol consumption and ethanol relapse. Recently, we reported that basal GABAergic transmission was increased in ethanol-dependent rats, and that acute ethanol increases GABAA receptor-mediated inhibitory postsynaptic currents (IPSCs) in CeA neurons from both naïve and ethanol-dependent rats to the same extent, suggesting lack of tolerance for the acute effect of ethanol. Here, we investigated the effect of nociceptin on IPSCs in CeA neurons and its interaction with ethanol effects on these GABA synapses. We found that nociceptin moderately decreased IPSC amplitudes, acting mostly presynaptically as it increased paired-pulse facilitation ratio of IPSCs and decreased miniature IPSC frequencies (but not amplitudes). Nociceptin also prevented the ethanol-induced augmentation of IPSCs in CeA of naïve rats. Interestingly, in CeA of ethanol-dependent rats, the nociceptin-induced inhibition of IPSCs was increased, indicating an enhanced sensitivity to nociceptin. Nociceptin also blocked the ethanol-induced augmentation of IPSCs in ethanol-dependent rats. Our data suggest that nociceptin has a role in regulating the GABAergic system and opposing the effect elicited by ethanol. Thus, nociceptin may represent a therapeutic target for alleviating alcohol dependence.

Patterns of gene expression in the frontal cortex discriminate alcoholic from nonalcoholic individuals - Liu, Jianwen; Lewohl, Joanne M.; Harris, R. Adron; Iyer, Vishwanath R.; Dodd, Peter R.; Randall, Patrick K.; Mayfield, R. Dayne (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2006)
Alcohol dependence is characterized by tolerance, physical dependence, and craving. The neuroadaptations underlying these effects of chronic alcohol abuse are likely due to altered gene expression. Previous gene expression studies using human post-mortem brain demonstrated that several gene families were altered by alcohol abuse. However, most of these changes in gene expression were small. It is not clear if gene expression profiles have sufficient power to discriminate control from alcoholic individuals and how consistent gene expression changes are when a relatively large sample size is examined. In the present study, microarray analysis (approximately 47,000 elements) was performed on the superior frontal cortex of 27 individual human cases (14 well characterized alcoholics and 13 matched controls). A partial least squares statistical procedure was applied to identify genes with altered expression levels in alcoholics. We found that genes involved in myelination, ubiquitination, apoptosis, cell adhesion, neurogenesis, and neural disease showed altered expression levels. Importantly, genes involved in neurodegenerative diseases such as Alzheimer's disease were significantly altered suggesting a link between alcoholism and other neurodegenerative conditions. A total of 27 genes identified in this study were previously shown to be changed by alcohol abuse in previous studies of human post-mortem brain. These results revealed a consistent re-programming of gene expression in alcohol abusers that reliably discriminates alcoholic from non-alcoholic individuals.
Keywords: 80 and over; Adult; Aged; alcoholism; Case-Control Studies; Female; Frontal Lobe; Gene Expression; Gene Expression Profiling; Gene Expression Regulation; Humans; Male; Messenger; Middle Aged; Oligonucleotide Array Sequence Analysis; Postmortem Changes; RNA

PI3K signaling and miRNA expression during the response of quiescent human fibroblasts to distinct proliferative stimuli - Gu, Jian; Iyer, Vishwanath R. (Genome Biology, 2006)
BACKGROUND: Serum treatment of quiescent human dermal fibroblasts induces proliferation, coupled with a complex physiological response that is indicative of their normal role in wound-healing. However, it is not known to what extent such complex transcriptional events are specific to a given cell type and signal, and how these global changes are coordinately regulated. We have profiled the global transcriptional program of human fibroblasts from two different tissue sources to distinct growth stimuli, and identified a striking conservation in their gene-expression signatures. RESULTS: We found that the wound-healing program of gene expression was not specific to the response of dermal fibroblasts to serum but was regulated more broadly. However, there were specific differences among different stimuli with regard to signaling pathways that mediate these transcriptional programs. Our data suggest that the PI3-kinase pathway is differentially involved in mediating the responses of cells to serum as compared with individual peptide growth factors. Expression profiling indicated that let7 and other miRNAs with similar expression profiles may be involved in regulating the transcriptional program in response to proliferative signals. CONCLUSION: This study provides insights into how different stimuli use distinct as well as conserved signaling and regulatory mechanisms to mediate genome-wide transcriptional reprogramming during cell proliferation. Our results indicate that conservation of transcriptional programs and their regulation among different cell types may be much broader than previously appreciated.
Keywords: Cell Line; Cell Proliferation; Chromones; Enzyme Inhibitors; Fibroblasts; Gene Expression; Gene Expression Profiling; Gene Expression Regulation; Genetic; Growth Substances; Humans; Lung; MicroRNAs; Morpholines; Phosphatidylinositol 3-Kinases; Signal Transduction; Skin; Transcription; Wound Healing

Preliminary data on the association among the serotonin transporter polymorphism, subjective alcohol experiences, and drinking behavior - Corbin, William R.; Fromme, Kim; Bergeson, Susan E. (Journal of Studies on Alcohol, 2006)
OBJECTIVE: Individual differences in subjective responses to alcohol are believed to have a genetic basis and have been associated with increased risk of alcohol-related problems. There are, however, conflicting results from past studies, perhaps owing to differences in subjective alcohol effects by limb of the blood alcohol curve and the passage of time. The current pilot study evaluated relations among serotonin transporter (SERT) genotype, subjective alcohol responses, and drinking behavior across both the ascending and descending limbs of the blood alcohol curve. METHOD: Participants (N=222; 68% male) were administered alcohol (target blood alcohol concentration of .06%) with a subsample (n=86) providing genetic data. Following a social stressor, participants were provided the opportunity to engage in ad libitum alcohol consumption. RESULTS: SERT transporter was not significantly associated with ad lib drinking or subjective alcohol effects at individual time points, although a trend toward a SERT by blood alcohol concentration limb interaction was observed for ad lib drinking. In addition, SERT genotype predicted acute tolerance to alcohol effects, with participants homozygous for the long SERT allele developing acute tolerance more rapidly than other genotypes. CONCLUSIONS: Although SERT genotype was not reliably associated with ad lib drinking behavior, the results suggest that individuals with the long-long (LL) genotype may develop acute tolerance to alcohol effects more rapidly than heterozygotes or individuals homozygous for the short SERT allele.
Keywords: Affect; Alcohol Drinking; alcoholism; Alleles; Female; Genetic; Genotype; Humans; Male; Polymerase Chain Reaction; Polymorphism; Serotonin; Serotonin Plasma Membrane Transport Proteins; Surveys and Questionnaires

Protein expression changes in the nucleus accumbens and amygdala of inbred alcohol-preferring rats given either continuous or scheduled access to ethanol - Bell, R. L.; Kimpel, M. W.; Rodd, Z. A.; Strother, W. N.; Bai, F.; Peper, C. L.; Mayfield, R. D.; Lumeng, L.; Crabb, D. W.; McBride, W. J.; Witzmann, F. A. (Alcohol (Fayetteville, N.Y.), 2006)
Chronic ethanol (EtOH) drinking produces neuronal alterations within the limbic system. To investigate changes in protein expression levels associated with EtOH drinking, inbred alcohol-preferring (iP) rats were given one of three EtOH access conditions in their home-cages: continuous ethanol (CE: 24h/day, 7days/week access to EtOH), multiple scheduled access (MSA: four 1-h sessions during the dark cycle/day, 5 days/week) to EtOH, or remained EtOH-naïve. Both MSA and CE groups consumed between 6 and 6.5g of EtOH/kg/day after the 3rd week of access. On the first day of EtOH access for the seventh week, access was terminated at the end of the fourth MSA session for MSA rats and the corresponding time point (2300h) for CE rats. Ten h later, the rats were decapitated, brains extracted, the nucleus accumbens (NAcc) and amygdala (AMYG) microdissected, and protein isolated for 2-dimensional gel electrophoretic analyses. In the NAcc, MSA altered expression levels for 12 of the 14 identified proteins, compared with controls, with six of these proteins altered by CE access, as well. In the AMYG, CE access changed expression levels for 22 of the 27 identified proteins, compared with controls, with 8 of these proteins altered by MSA, as well. The proteins could be grouped into functional categories of chaperones, cytoskeleton, intracellular communication, membrane transport, metabolism, energy production, or neurotransmission. Overall, it appears that EtOH drinking and the conditions under which EtOH is consumed, differentially affect protein expression levels between the NAcc and AMYG. This may reflect differences in neuroanatomical and/or functional characteristics associated with EtOH self-administration and possibly withdrawal, between these two brain structures.
Keywords: Alcohol Drinking; Amygdala; Animals; Biomarkers; Central Nervous System Depressants; Cytoskeletal Proteins; Drug Administration Schedule; Electrophoresis; Enzymes; Ethanol; Female; Gel; Inbred Strains; Intracellular Signaling Peptides and Proteins; Membrane Transport Proteins; Molecular Chaperones; Nerve Tissue Proteins; Nucleus Accumbens; Peptide Mapping; Proteins; Proteomics; Rats; Self Administration; Time Factors; Two-Dimensional

Reduced alcohol consumption in mice lacking preprodynorphin. - Blednov, Yuri A.; Walker, Danielle; Martinez, Marni; Harris., R. Adron (Alcohol (Fayetteville, N.Y.), 2006)
Many studies suggest a role for endogenous opioid peptides and their receptors in regulation of ethanol intake. It is commonly accepted that the κ-opioid receptors and their endogenous ligands, dynorphins, produce a dysphoric state and therefore may be responsible for avoidance of alcohol. We used mutant mice lacking preprodynorphin in a variety of behavioral tests of alcohol actions. Null mutant female, but not male, mice showed significantly lower preference for alcohol and consumed lower amounts of alcohol in a two-bottle choice test as compared with wild-type littermates. In the same test, knockout mice of both sexes showed a strong reduction of preference for saccharin compared to control mice. In contrast, under conditions of limited (4 hours) access (light phase of the light/dark cycle), null mutant mice did not show any differences in consumption of saccharin but they showed significantly reduced intake of sucrose. To determine the possible cause for reduction of ethanol preference and intake, we studied other ethanol-related behaviors in mice lacking the preprodynorphin gene. There were no differences between null mutant and wild type mice in ethanol-induced loss of righting reflex, acute ethanol withdrawal, ethanol-induced conditioned place preference or conditioned taste aversion to ethanol. These results indicate that deletion of preprodynorphin leads to substantial reduction of alcohol intake in female mice, and suggest thath this is caused by decreased orosensory reward of alcohol (sweet taste and/or palatability).

Reduced basal and ethanol stimulation of striatal extracellular dopamine concentrations in dopamine D2 receptor knockout mice - Job, Martin O.; Ramachandra, Vorani; Anders, Sheneil; Low, Malcolm J.; Gonzales, Rueben A. (Synapse (New York, N.Y.), 2006)
The present study was undertaken to examine the role of the dopamine (DA) D2 receptor in the ethanol-evoked DA response in the ventral striatum. We performed microdialysis experiments using the D2 null mutant and wild-type controls and measured the effect of an intraperitoneal (i.p.) injection of either saline or ethanol (2 g/kg) on dialysate DA concentrations in the ventral striatum. Dialysate ethanol concentrations were also determined in the samples from the ventral striatum. In addition, the effects of quinpirole, a D2/D3 agonist, were examined in both the ventral and dorsal striatum. Basal dialysate concentrations of DA were significantly reduced in both the ventral and dorsal striatum of the D2 knockouts compared with wild-type controls. Ethanol administration significantly enhanced ventral striatal DA in both groups, but the increase in dialysate DA concentration was 3.5-fold higher in the wild-type controls. The time course of dialysate ethanol concentrations was similar in the two groups. Saline injection did not alter DA concentrations in either the ventral or dorsal striatum. However, quinpirole (0.3 mg/kg) administration significantly depressed striatal dialysate DA concentrations in the wild-type mice, but not in the D2 knockouts. The results suggest that the D2 receptor is necessary for normal development and regulation of striatal extracellular DA concentrations, but the mechanism for this alteration is unclear. In addition, the blunted ethanol-evoked DA response in the D2 knockouts may contribute, in part, to some of the behavioral deficits previously observed in response to ethanol.
Keywords: Alcohol-Induced Disorders; Animal; Animals; Basal Ganglia; Calcium; Calcium Signaling; Central Nervous System Depressants; Disease Models; dopamine; Dopamine Agonists; Dopamine D2; Dose-Response Relationship; Down-Regulation; Drug; Ethanol; Extracellular Fluid; Knockout; Mice; Nervous System; Neural Pathways; Nucleus Accumbens; Quinpirole; Receptors; Ventral tegmental area

Reestablishing an intragastric ethanol self-infusion model in rats - Fidler, Tara L.; Clews, Tara W.; Cunningham, Christopher L. (Alcoholism, Clinical and Experimental Research, 2006)
BACKGROUND: There is a scarcity of behavioral models that will reliably produce ethanol intakes in rodents at levels that induce or maintain dependence. The present experiments were designed to reestablish a model that uses passive intragastric (IG) infusion of ethanol to induce tolerance/dependence/withdrawal before allowing rats to self-infuse ethanol intragastrically. METHODS: Sprague-Dawley rats were surgically implanted with IG catheters and allowed to recover. During the passive infusion phase (3-6 days), rats in the experimental group were passively infused with 10% (v/v) ethanol (3.3-12.2 g/kg/d). Rats in the control group were not infused. During the self-infusion phase (5-6 days), all rats had access to 2 flavored solutions. Licks on 1 solution were paired with ethanol infusions (20%, v/v) whereas licks on the other solution were unpaired. Experiments differed in the specific passive infusion parameters and in the ethanol intake limit during self-infusion. RESULTS: Rats in the experimental groups self-infused more ethanol per day (means of 4-7 g/kg/d) than did rats in the control group (means of 0-2.6 g/kg/d). Across all 3 studies, individual total daily intakes exceeded 5 g/kg on 35% of the self-infusion days in ethanol-preexposed rats compared with <1% of the self-infusion days in the control rats. Ethanol-exposed rats also infused a substantially higher percentage (42%) of their total ethanol intake in relatively large bouts (>1.5 g/kg) compared with control rats (<10%). The addition of a daily 6-hour ethanol-free period during the passive infusion phase (in Experiments 2 and 3) led to higher ethanol intakes than in Experiment 1. Results of a control experiment showed that differences between experimental and control groups in Experiments 1 to 3 were a result of ethanol experience and not a general effect of differential infusion experience. CONCLUSIONS: Relatively short periods of passive IG infusion of ethanol induced levels of ethanol self-infusion in genetically heterogeneous rats that were comparable with drinking intakes previously reported in rats selectively bred for ethanol intake/preference. Although the induction of dependence/withdrawal may have played a role in this outcome, an alternative interpretation is that experimental rats self-infused more ethanol because passive exposure produced tolerance to aversive pharmacological effects that would otherwise limit intake of the paired flavor because of development of conditioned taste aversion. The current findings provide a strong basis for future work designed to identify parametric determinants of this form of self-administration, its sensitivity to genetic influences, and its neurobiological substrates.
Keywords: Alcoholic Intoxication; alcoholism; Animals; Central Nervous System Depressants; Ethanol; Gastrointestinal; Habituation; Intubation; Male; Psychophysiologic; Rats; Recurrence; Reinforcement (Psychology); Reinforcement Schedule; Self Administration; Sprague-Dawley; Substance Withdrawal Syndrome; Time Factors

A sex-specific role of type VII adenylyl cyclase in depression - Hines, Lisa M.; Hoffman, Paula L.; Bhave, Sanjiv; Saba, Laura; Kaiser, Alan; Snell, Larry; Goncharov, Igor; LeGault, Lucie; Dongier, Maurice; Grant, Bridget; Pronko, Sergey; Martinez, Larry; et al. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2006)
Major depression represents a complex mental disorder. The identification of biological markers that define subtypes of major depressive disorder would greatly facilitate appropriate medical treatments, as well as provide insight into etiology. Reduced activity of the cAMP signaling system has been implicated in the etiology of major depression. Previous work has shown low adenylyl cyclase activity in platelets and postmortem brain tissue of depressed individuals. Here, we investigate the role of the brain type VII isoform of adenylyl cyclase (AC7) in the manifestation of depressive symptoms in genetically modified animals, using a combination of in vivo behavioral experiments, gene expression profiling, and bioinformatics. We also completed studies with humans on the association of polymorphisms in the AC7 gene with major depressive illness (unipolar depression) based on Diagnostic and Statistical Manual of Mental Disorders IV criteria. Collectively, our results demonstrate a sex-specific influence of the AC7 gene on a heritable form of depressive illness.
Keywords: Adenylyl Cyclases; Adult; Amino Acid Sequence; Animals; Depressive Disorder; Female; Genetic Linkage; Humans; Inbred C57BL; Major; Male; Mice; Middle Aged; Molecular Sequence Data; Polymorphism; Sex Characteristics; Single Nucleotide; Transgenic

Stability of inbred mouse strain differences in behavior and brain size between laboratories and across decades - Wahlsten, Douglas; Bachmanov, Alexander; Finn, Deborah A.; Crabbe, John C. (Proceedings of the National Academy of Sciences, 2006)
If we conduct the same experiment in two laboratories or repeat a classical study many years later, will we obtain the same results? Recent research with mice in neural and behavioral genetics yielded different results in different laboratories for certain phenotypes, and these findings suggested to some researchers that behavior may be too unstable for fine-scale genetic analysis. Here we expand the range of data on this question to additional laboratories and phenotypes, and, for the first time in this field, we formally compare recent data with experiments conducted 30–50 years ago. For ethanol preference and locomotor activity, strain differences have been highly stable over a period of 40–50 years, and most strain correlations are in the range of r = 0.85–0.98, as high as or higher than for brain weight. For anxiety-related behavior on the elevated plus maze, on the other hand, strain means often differ dramatically across laboratories or even when the same laboratory is moved to another site within a university. When a wide range of phenotypes is considered, no inbred strain appears to be exceptionally stable or labile across laboratories in any general sense, and there is no tendency to observe higher correlations among studies done more recently. Phenotypic drift over decades for most of the behaviors examined appears to be minimal.
Keywords: agonistic behavior; Anxiety; ethanol preference; gene–environment interaction; locomotor activity

Structural and functional modifications in glutamateric synapses following prolonged ethanol exposure - Chandler, L. Judson; Carpenter-Hyland, Ezekiel; Hendricson, Adam W.; Maldve, Regina E.; Morrisett, Richard A.; Zhou, Feng C.; Sari, Youssef; Bell, Richard; Szumlinski, Karen K. (Alcoholism, Clinical and Experimental Research, 2006)
This article summarizes the proceedings of a symposium presented at the 2005 annual meeting of the Research Society on Alcoholism in Santa Barbara, California, USA. The organizer and chair was L. Judson Chandler. The presentations were (1) Chronic Ethanol Exposure, N-Methyl-D-Aspartate (NMDA) Receptor Dynamics, and Withdrawal Hyperexcitability, by Adam Hendricson, Regina Maldve, and Richard Morrisett; (2) Ethanol-Induced Synaptic Targeting of NMDA Receptors Is Associated With Enhanced Postsynaptic Density-95 Clustering and Spine Size, by Judson Chandler and Ezekiel Carpenter-Hyland; (3) Presynaptic and Postsynaptic Alterations in the Nucleus Accumbens Following Chronic Alcohol Exposure, by Feng Zhou, Youssef Sari, and Richard Bell; and (4) An Active Role for Accumbens Homer2 Expression in Alcohol-Induced Neural Plasticity, by Karen Szumlinski.
Keywords: Alcohol Withdrawal Delirium; alcoholism; Amygdala; Animals; Brain; Brain Mapping; Carrier Proteins; Ethanol; Glutamic Acid; Homer Scaffolding Proteins; Humans; Mice; N-Methyl-D-Aspartate; Neuronal Plasticity; Nucleus Accumbens; Rats; Receptors; Synapses

Toward understanding the genetics of alcohol drinking through transcriptome meta-analysis - Mulligan, Megan K.; Ponomarev, Igor; Hitzemann, Robert J.; Belknap, John K.; Tabakoff, Boris; Harris, R. Adron; Crabbe, John C.; Blednov, Yuri A.; Grahame, Nicholas J.; Phillips, Tamara J.; Finn, Deborah A.; Hoffman, Paula L.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
Much evidence from studies in humans and animals supports the hypothesis that alcohol addiction is a complex disease with both hereditary and environmental influences. Molecular determinants of excessive alcohol consumption are difficult to study in humans. However, several rodent models show a high or low degree of alcohol preference, which provides a unique opportunity to approach the molecular complexities underlying the genetic predisposition to drink alcohol. Microarray analyses of brain gene expression in three selected lines, and six isogenic strains of mice known to differ markedly in voluntary alcohol consumption provided >4.5 million data points for a meta-analysis. A total of 107 arrays were obtained and arranged into six experimental data sets, allowing the identification of 3,800 unique genes significantly and consistently changed between all models of high or low amounts of alcohol consumption. Several functional groups, including mitogen-activated protein kinase signaling and transcription regulation pathways, were found to be significantly overrepresented and may play an important role in establishing a high level of voluntary alcohol drinking in these mouse models. Data from the general meta-analysis was further filtered by a congenic strain microarray set, from which cis-regulated candidate genes for an alcohol preference quantitative trait locus on chromosome 9 were identified: Arhgef12, Carm1, Cryab, Cox5a, Dlat, Fxyd6, Limd1, Nicn1, Nmnat3, Pknox2, Rbp1, Sc5d, Scn4b, Tcf12, Vps11, and Zfp291 and four ESTs. The present study demonstrates the use of (i) a microarray meta-analysis to analyze a behavioral phenotype (in this case, alcohol preference) and (ii) a congenic strain for identification of cis regulation.

Transcriptional signatures of cellular plasticity in mice lacking the alpha1 subunit of GABAA receptors - Ponomarev, Igor; Maiya, Rajani; Harnett, Mark T.; Schafer, Gwen L.; Ryabinin, Andrey E.; Blednov, Yuri A.; Morikawa, Hitoshi; Boehm, Stephen L.; Homanics, Gregg E.; Berman, Ari E.; Berman, Ari; Lodowski, Kerrie H.; et al. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2006)
GABAA receptors mediate the majority of inhibitory neurotransmission in the CNS. Genetic deletion of the alpha1 subunit of GABAA receptors results in a loss of alpha1-mediated fast inhibitory currents and a marked reduction in density of GABAA receptors. A grossly normal phenotype of alpha1-deficient mice suggests the presence of neuronal adaptation to these drastic changes at the GABA synapse. We used cDNA microarrays to identify transcriptional fingerprints of cellular plasticity in response to altered GABAergic inhibition in the cerebral cortex and cerebellum of alpha1 mutants. In silico analysis of 982 mutation-regulated transcripts highlighted genes and functional groups involved in regulation of neuronal excitability and synaptic transmission, suggesting an adaptive response of the brain to an altered inhibitory tone. Public gene expression databases permitted identification of subsets of transcripts enriched in excitatory and inhibitory neurons as well as some glial cells, providing evidence for cellular plasticity in individual cell types. Additional analysis linked some transcriptional changes to cellular phenotypes observed in the knock-out mice and suggested several genes, such as the early growth response 1 (Egr1), small GTP binding protein Rac1 (Rac1), neurogranin (Nrgn), sodium channel beta4 subunit (Scn4b), and potassium voltage-gated Kv4.2 channel (Kcnd2) as cell type-specific markers of neuronal plasticity. Furthermore, transcriptional activation of genes enriched in Bergman glia suggests an active role of these astrocytes in synaptic plasticity. Overall, our results suggest that the loss of alpha1-mediated fast inhibition produces diverse transcriptional responses that act to regulate neuronal excitability of individual neurons and stabilize neuronal networks, which may account for the lack of severe abnormalities in alpha1 null mutants.
Keywords: Animals; GABA-A; Gene Expression Profiling; Knockout; Male; Mice; Neural Inhibition; Neuroglia; Neuronal Plasticity; Neurons; Receptors; Synaptic Transmission; Transcription Factors

Urocortin 1 in the dorsal raphe regulates food and fluid consumption, but not ethanol preference in C57BL/6J mice - Weitemier, A. Z.; Ryabinin, A. E. (Neuroscience, 2006)
The midbrain-localized Edinger-Westphal nucleus is a major site of production of urocortin 1. Urocortin 1 is a neuropeptide related to corticotropin-releasing factor that has high affinity for corticotropin-releasing factor type-1 and corticotropin-releasing factor type-2 receptors. In several mouse models, the amount of urocortin 1 neurons within the Edinger-Westphal nucleus is positively associated with ethanol preference. Central administration of urocortin 1 exerts potent anorectic actions, and implicates endogenous urocortin 1 in the regulation of food intake. It is possible that brain areas such as the dorsal raphe, which receives urocortin 1 from the Edinger-Westphal nucleus and highly expresses corticotropin-releasing factor type-2 receptors, mediate the actions of urocortin 1 on feeding and ethanol preference. In this study the amount of food, water and ethanol consumed over the dark cycle by ethanol-preferring C57BL/6J mice was measured after injection of artificial cerebrospinal fluid vehicle, urocortin 1, corticotropin-releasing factor and the corticotropin-releasing factor type-2 receptor-selective antagonist antisauvagine-30 onto the dorsal raphe. Compared with vehicle, corticotropin-releasing factor and antisauvagine-30, urocortin 1 induced a significant reduction in the amount of food consumed overnight. Also, compared with antisauvagine-30 treatment, urocortin 1 significantly reduced the amount of weight gained during this time. Urocortin 1 also significantly reduced the total amount of fluid consumed, but did not alter ethanol preference, which was high during all treatments. These results suggest that the dorsal raphe is a neuroanatomical substrate of urocortin 1-induced reductions in feeding, possibly through modulation of serotonergic activity from this nucleus. In addition, it is suggested that endogenous urocortin 1 in this area, such as from the Edinger-Westphal nucleus, does not regulate ethanol preference in C57BL/6J mice.
Keywords: Alcohol Drinking; Animals; Appetite; Corticotropin-Releasing Hormone; Drinking Behavior; Ethanol; FEEDING BEHAVIOR; Humans; Inbred C57BL; Male; Mice; Microinjections; Peptides; Raphe Nuclei; Rats; Urocortins; Weight Gain

The urocortin 1 neurocircuit: ethanol-sensitivity and potential involvement in alcohol consumption - Ryabinin, Andrey E.; Weitemier, Adam Z. (Brain Research Reviews, 2006)
One of the hallmarks of alcoholism is continued excessive consumption of alcohol-containing beverages despite the negative consequences of such behavior. The neurocircuitry regulating alcohol consumption is not well understood. Recent studies have shown that the neuropeptide urocortin 1 (Ucn1), a member of the corticotropin-releasing factor (CRF) family of peptides, could be an important player in the regulation of alcohol consumption. This evidence is accumulated along three directions of research: (1) Ucn 1-containing neurons are extremely sensitive to alcohol; (2) the Ucn1 neurocircuit may contribute to the genetic predisposition to high alcohol intake in mice and rats; (3) manipulation of the Ucn1 system alters alcohol consumption and sensitivity. This paper reviews the current knowledge of the Ucn1 neurocircuit and the evidence for its involvement in alcohol-related behaviors, and proposes a mechanism for its involvement in the regulation of alcohol consumption.
Keywords: Alcohol-Induced Disorders; alcoholism; Animal; Animals; Brain; Corticotropin-Releasing Hormone; Disease Models; Ethanol; Genetic Predisposition to Disease; Humans; Mice; Models; Nervous System; Neural Pathways; Neurological; Rats; Urocortins

Alcohol effects on central nervous system gene expression in genetic animal models - McBride, William J.; Kerns, Robnet T.; Rodd, Zachary A.; Strother, Wendy N.; Edenberg, Howard J.; Hashimoto, Joel G.; Wiren, Kristine M.; Miles, Michael F. (Alcoholism, Clinical and Experimental Research, 2005)
This article summarizes the proceedings of a symposium presented at the 2004 annual meeting of the Research Society on Alcoholism in Vancouver, British Columbia, Canada. The organizers and chairs were William J. McBride and Michael F. Miles. The presentations were (1) Molecular Triangulation on Gene Expression Patterns in Behavioral Responses to Acute Ethanol, by Robnet T. Kerns; (2) Gene Expression in Limbic Regions After Ethanol Self-Infusion Into the Posterior Ventral Tegmental Area, by Zachary A. Rodd; (3) Microarray Analysis of CNS Limbic Regions of Inbred Alcohol-Preferring and -Nonpreferring rats and Effects of Alcohol Drinking, by Wendy N. Strother and Howard J. Edenberg; and (4) Microarray Analysis of Mouse Lines Selected for Chronic Ethanol Withdrawal Severity: The Convergence of Basal, Ethanol Regulated, and Proximity to Ethanol Quantitative Trait Loci to Identify Candidate Genes, by Joel G. Hashimoto and Kristine M. Wiren.
Keywords: alcoholism; Animal; Animals; Behavior; Central Nervous System; Disease Models; Gene Expression Regulation; Oligonucleotide Array Sequence Analysis; Quantitative Trait Loci; Severity of Illness Index; Substance Withdrawal Syndrome

Alcohol withdrawal and conditioning - Little, Hilary J.; Stephens, David N.; Ripley, Tamzon L.; Borlikova, Gilyana; Duka, Theodora; Schubert, Manja; Albrecht, Doris; Becker, Howard C.; Lopez, Marcello F.; Weiss, Friedbert; Drummond, Colin; Peoples, Michelle; et al. (Alcoholism, Clinical and Experimental Research, 2005)
This review contains the proceedings from a symposium held at the RSA conference in 2003 on "Alcohol Withdrawal and Conditioning." The presentations covered a range of interactions between conditioning and alcohol withdrawal, in both animal behavior and the clinic. Dr. D.N. Stephens first described his studies exploring the consequences of alcohol dependence and repeated experience of withdrawal on the conditioning process. His data suggested that repeated withdrawal from moderate alcohol intake impairs amygdala-dependent mechanisms for learning about aversive events. Dr. H. Becker then detailed studies examining the consequences of repeated ethanol withdrawal experience on subsequent ethanol drinking behavior in mice, and conditions in which motivational properties of odor cues that are associated with different phases of ethanol withdrawal influence such relapse behavior. The data suggested that cues associated with acute withdrawal or "recovery" from withdrawal may serve as modulating factors in influencing subsequent ethanol drinking behavior, and that the timing of the cues determines their consequences. Dr. F. Weiss described recent findings from animal models of relapse that suggested the efficacy of alcohol-associated contextual stimuli in eliciting alcohol-seeking behavior resembles the endurance of conditioned cue reactivity and cue-induced cocaine craving in humans. The interactive effects of stress and ethanol-related environmental stimuli were found to be dependent on concurrent activation of endogenous opioid and corticotropin-releasing factor systems. Conditioning factors (i.e., exposure to drug-associated stimuli) and stress could therefore interact to augment vulnerability to relapse. Dr. C. Drummond then addressed the clinical aspects of conditioning during alcohol withdrawal and described studies showing exposure of alcoholics to alcohol-related cues elicited greater subjective and physiological responses than exposure to neutral cues. The former responsivity showed a relationship with a measure of motivation to drink alcohol. Finally, Dr. C. Cunningham provided a summary of the concepts involved in the presentations and discussed the conditioning processes that affect behavior during and after alcohol withdrawal.
Keywords: Alcohol Drinking; alcoholism; Animals; Avoidance Learning; Central Nervous System Depressants; Conditioning; Ethanol; Operant; Rats; Substance Withdrawal Syndrome

Alcohol withdrawal severity in inbred mouse (Mus musculus) strains - Metten, Pamela; Crabbe, John C. (Behavioral Neuroscience, 2005)
Male mice (Mus musculus) from 15 standard inbred strains were exposed to a nearly constant concentration of ethanol (EtOH) vapor for 72 hr, averaging 1.59 +/- 0.03 mg EtOH/mL blood at withdrawal. EtOH- and air-exposed groups were tested hourly for handling-induced convulsions for 10 hr and at Hours 24 and 25. Strains differed markedly in the severity of withdrawal (after subtraction of control values), and by design these differences were independent of strain differences in EtOH metabolism. Correlation of strain mean withdrawal severity with other responses to EtOH supported previously reported genetic relationships of high EtOH withdrawal with low drinking, high conditioned taste aversion, low tolerance to EtOH-induced hypothermia, and high stimulated activity after low-dose EtOH. Also supported were the positive genetic correlations among EtOH, barbiturate, and benzodiazepine withdrawal. Sensitivity of naive mice to several chemical convulsant-induced seizures was also correlated with EtOH withdrawal.
Keywords: Alcohol Withdrawal Delirium; Alcohol-Induced Disorders; Analysis of Variance; Animal; Animals; Central Nervous System Depressants; Disease Models; Dose-Response Relationship; Drug; Ethanol; Inbred Strains; Male; Mice; Severity of Illness Index; Species Specificity; Statistics as Topic; Time Factors

Alcoholic neurobiology: changes in dependence and recovery - Crews, Fulton T.; Buckley, Tracey; Dodd, Peter R.; Ende, Gabriele; Foley, Nina; Harper, Clive; He, Jun; Innes, David; Loh, El-Wui; Pfefferbaum, Adolph; Zou, Jian; Sullivan, Edith V. (Alcoholism, Clinical and Experimental Research, 2005)
This article presents the proceedings of a symposium held at the meeting of the International Society for Biomedical Research on Alcoholism (ISBRA) in Mannheim, Germany, in October, 2004. Chronic alcoholism follows a fluctuating course, which provides a naturalistic experiment in vulnerability, resilience, and recovery of human neural systems in response to presence, absence, and history of the neurotoxic effects of alcoholism. Alcohol dependence is a progressive chronic disease that is associated with changes in neuroanatomy, neurophysiology, neural gene expression, psychology, and behavior. Specifically, alcohol dependence is characterized by a neuropsychological profile of mild to moderate impairment in executive functions, visuospatial abilities, and postural stability, together with relative sparing of declarative memory, language skills, and primary motor and perceptual abilities. Recovery from alcoholism is associated with a partial reversal of CNS deficits that occur in alcoholism. The reversal of deficits during recovery from alcoholism indicates that brain structure is capable of repair and restructuring in response to insult in adulthood. Indirect support of this repair model derives from studies of selective neuropsychological processes, structural and functional neuroimaging studies, and preclinical studies on degeneration and regeneration during the development of alcohol dependence and recovery form dependence. Genetics and brain regional specificity contribute to unique changes in neuropsychology and neuroanatomy in alcoholism and recovery. This symposium includes state-of-the-art presentations on changes that occur during active alcoholism as well as those that may occur during recovery-abstinence from alcohol dependence. Included are human neuroimaging and neuropsychological assessments, changes in human brain gene expression, allelic combinations of genes associated with alcohol dependence and preclinical studies investigating mechanisms of alcohol induced neurotoxicity, and neuroprogenetor cell expansion during recovery from alcohol dependence.
Keywords: Adult; Alcoholic Intoxication; alcoholism; Brain Mapping; DNA Repair; Ethanol; GABA-A; Gene Expression Regulation; Humans; Magnetic Resonance Imaging; Memory; Motivation; Nerve Degeneration; Nerve Regeneration; Neurons; Neuropsychological Tests; Orientation; Receptors; Short-Term; Substance Withdrawal Syndrome

Ataxia and c-Fos expression in mice drinking ethanol in a limited access session - Sharpe, Amanda L.; Tsivkovskaia, Natalia O.; Ryabinin, Andrey E. (Alcoholism, Clinical and Experimental Research, 2005)
BACKGROUND: Although previous murine studies have demonstrated ethanol self-administration resulting in blood ethanol concentrations (BECs) believed to be pharmacologically relevant, to our knowledge, no study reported to date has demonstrated intoxication via ataxia after self-administration. Thus, the goal of this study was to demonstrate ataxia and to examine changes in c-Fos expression in mice after self-administration of intoxicating doses of ethanol. METHODS: Male C57BL/6J mice were trained to drink a 10% ethanol solution during daily 30-min limited access sessions. Mice were exposed to increasing concentrations of ethanol until a 10% ethanol solution was reached. BEC and ataxia, measured as foot slips off of a balance beam, were examined after the limited access self-administration session. In a separate experiment, various brain structures from mice drinking water or ethanol were examined for changes in c-Fos expression two hr after the limited access session. RESULTS: Mice drank between 1.5 and 2 g/kg of 10% ethanol during the daily 30-min session. BECs for these mice 15 min after the limited access session ranged between 0.52 and 2.13 mg/ml. A significant increase in foot slips off a balance beam was seen immediately after ethanol consumption during the limited access session. Among mice drinking ethanol, an increase in c-Fos expression was seen in the Edinger-Westphal nucleus, and a decrease in c-Fos expression was seen in the cingulate cortex, ventral tegmental area, lateral and medial septum, CA1 region of the hippocampus, and basolateral amygdala. CONCLUSIONS: After this procedure in mice, BECs are achieved that are in a range considered pharmacologically relevant and intoxicating. Significant ataxia was observed after ethanol self-administration. Brain regions showing changes in c-Fos expression after voluntary intoxication were similar to those previously reported, suggesting that these brain regions are involved in regulating behavioral effects of alcohol intoxication.
Keywords: Alcohol Drinking; Alcoholic Intoxication; Animals; Ataxia; Brain; Brain Mapping; Dose-Response Relationship; Drug; Ethanol; fos; Gene Expression Regulation; Genes; Inbred C57BL; Male; Mice; Motor Skills; Postural Balance

Brain Region–Specific Regulation of Urocortin 1 Innervation and Corticotropin-Releasing Factor Receptor Type 2 Binding by Ethanol Exposure - Weitemier, Adam Z.; Ryabinin, Andrey E. (Alcoholism: Clinical and Experimental Research, 2005)
Background: Ethanol administration and consumption selectively activates the urocortin 1 (Ucn1)-expressing neurons of the Edinger-Westphal nucleus. We investigated whether repeated ethanol exposure affects Ucn1 and Ucn1-responsive corticotropin-releasing factor type-2 receptors (CRF2). Methods: Male C57BL/6J and DBA/2J mice were exposed to 2 g/kg ethanol via intraperitoneal injection once per day for 14, seven, or zero days. Ucn1 immunoreactivity was measured in the lateral septum, dorsal raphe, and Edinger-Westphal nucleus. In a separate experiment, C57BL/6J mice were exposed to ethanol for seven, one, or zero days, and CRF2 receptor binding was measured in the lateral septum and dorsal raphe by receptor autoradiography. Results: Ethanol exposure induced parallel changes in Ucn1 immunoreactive terminal fibers in the lateral septum and dorsal raphe of both strains. Seven ethanol exposures but not one ethanol exposure significantly increased CRF2 receptor binding in the dorsal raphe and slightly increased CRF2 receptor binding in the lateral septum. Conclusions: These results provide evidence that the Ucn1/CRF2 receptor system can be modified by ethanol exposure. They additionally suggest that this system may be involved in behavioral changes during alcoholism.

Chronic ethanol drinking by alcohol-preferring rats increases the sensitivity of the posterior ventral tegmental area to the reinforcing effects of ethanol - Rodd, Zachary A.; Bell, Richard L.; McQueen, Victoria K.; Davids, Michelle R.; Hsu, Cathleen C.; Murphy, James M.; Li, Ting-Kai; Lumeng, Lawrence; McBride, William J. (Alcoholism, Clinical and Experimental Research, 2005)
BACKGROUND: The ventral tegmental area (VTA) is involved in regulating ethanol drinking, and the posterior VTA seems to be a neuroanatomical substrate that mediates the reinforcing effects of ethanol in ethanol-naive Wistar and ethanol-naive alcohol-preferring (P) rats. The objective of this study was to test the hypothesis that chronic ethanol drinking increases the sensitivity of the posterior VTA to the reinforcing effects of ethanol. METHODS: Two groups of female P rats (one given water as its sole source of fluid and the other given 24-hr free-choice access to 15% ethanol and water for at least 8 weeks) were stereotaxically implanted with guide cannulae aimed at the posterior VTA. One week after surgery, rats were placed in standard two-lever (active and inactive) operant chambers and connected to the microinfusion system. Depression of the active lever produced the infusion of 100 nl of artificial cerebrospinal fluid (CSF) or ethanol. The ethanol-naive and chronic ethanol-drinking groups were assigned to subgroups to receive artificial CSF or 25, 50, 75, or 125 mg/dl of ethanol (n = 6-9/dose/group) to self-infuse (FR1 schedule) during the 4-hr sessions given every other day. RESULTS: Compared with the infusions of artificial CSF, the control group reliably (p < 0.05) self-infused 75 and 125 mg/dl of ethanol but not the lower concentrations. The ethanol-drinking group had significantly (p < 0.05) higher self-infusions of 50, 75, and 125 mg/dl of ethanol than artificial CSF during the four acquisition sessions; the number of infusions of all three doses was higher in the ethanol-drinking group than in the ethanol-naive group. Both groups decreased responding on the active lever when artificial CSF was substituted for ethanol, and both groups demonstrated robust reinstatement of responding on the active lever when ethanol was restored. CONCLUSIONS: Chronic ethanol drinking by P rats increased the sensitivity of the posterior VTA to the reinforcing effects of ethanol.
Keywords: Alcohol Drinking; Animals; Central Nervous System Depressants; Conditioning; dopamine; Dose-Response Relationship; Drug; Ethanol; Female; Infusions; Intravenous; Operant; Rats; Reinforcement (Psychology); Ventral tegmental area

Chronic Ethanol Exposure and Protracted Abstinence Alter NMDA Receptors in Central Amygdala - Roberto, Marisa; Bajo, Michal; Crawford, Elena; Madamba, Samuel G.; Siggins, George R. (Neuropsychopharmacology, 2005)
We recently reported that chronic ethanol treatment (CET) and early withdrawal (2–8 h) altered glutamatergic transmission at both pre- and postsynaptic sites in central nucleus of the amygdala (CeA). Acute ethanol (44 mM) inhibited the NMDA receptor (NMDAR)-mediated EPSCs (NMDA-EPSCs) more in CeA neurons from CET rats than from naïve rats and also decreased paired-pulse facilitation (PPF) of NMDA-EPSCs only in CET rats. To determine whether these CET effects persisted after prolonged withdrawal, we recorded intracellularly in rat CeA slices and measured mRNA and protein expression of CeA NMDAR subunits from CET rats and those withdrawn from ethanol for 1 or 2 weeks. At 1 week withdrawal, acute ethanol decreased evoked NMDA-EPSC amplitudes and NMDA currents induced by exogenous NMDA (20%) equally to that in naïve rats, indicating that CET effects on postsynaptic mechanisms reversed 1 week after CET cessation. However, acute ethanol still decreased PPF of NMDA-EPSCs, indicating that the acute ethanol-induced increase in glutamate release in CeA seen in CET rats was still present at this time. CET also significantly increased mRNA levels of NR1 and NR2B NMDAR subunits compared to control rats. At 1 week withdrawal, mRNA levels for NR1 and NR2B subunits were significantly decreased. These changes reversed at 2 weeks withdrawal. In Western blots, a significant increase in protein for all three subunits occurred in CeA from CET rats, but not after 1 and 2 weeks of withdrawal. These data indicate that CET induces reversible neuroadaptations in synaptic function, gene expression, and protein composition of NMDAR at CeA synapses.
Keywords: alcohol; Electrophysiology; ethanol dependence; paired-pulse facilitation; real-time PCR; Western blot

Complex genetics of interactions of alcohol and CNS function and behavior - Matthews, Douglas B.; Bhave, Sanjiv V.; Belknap, John K.; Brittingham, Cynthia; Chesler, Elissa J.; Hitzemann, Robert J.; Hoffmann, Paula L.; Lu, Lu; McWeeney, Shannon; Miles, Michael F.; Tabakoff, Boris; Williams, Robert W. (Alcoholism, Clinical and Experimental Research, 2005)
This work summarizes the proceedings of a symposium at the 2004 RSA Meeting in Vancouver, Canada. The organizers were R. W. Williams and D. B. Matthews; the Chair was M. F. Miles. The presentations were (1) WebQTL: A resource for analysis of gene expression variation and the genetic dissection of alcohol related phenotypes, by E. J. Chesler, (2) The marriage of microarray and qtl analyses: what's to gain, by J. K. Belknap, (3) Use of WebQTL to identify QTLs associated with footshock stress and ethanol related behaviors, by D. B. Matthews, (4) A high throughput strategy for the detection of quantitative trait genes, by R. J. Hitzemann, and (5) The use of gene arrays in conjunction with transgenic and selected animals to understand anxiety in alcoholism, by. B. Tabakoff.
Keywords: Adenylyl Cyclases; alcoholism; Animals; Brain; G Protein-Coupled Inwardly-Rectifying Potassium Channels; Gene Expression; Humans; Inwardly Rectifying; Oligonucleotide Array Sequence Analysis; Potassium Channels; Psychological; Quantitative Trait Loci; Sodium-Potassium-Exchanging ATPase; Stress

Dopamine D5 receptor localization on cholinergic neurons of the rat forebrain and diencephalon: a potential neuroanatomical substrate involved in mediating dopaminergic influences on acetylcholine release - Berlanga, Monica Lisa; Simpson, Taylor Kathryn; Alcantara, Adriana Angelica (The Journal of Comparative Neurology, 2005)
The study of dopaminergic influences on acetylcholine release is especially useful for the understanding of a wide range of brain functions and neurological disorders, including schizophrenia, Parkinson's disease, Alzheimer's disease, and drug addiction. These disorders are characterized by a neurochemical imbalance of a variety of neurotransmitter systems, including the dopamine and acetylcholine systems. Dopamine modulates acetylcholine levels in the brain by binding to dopamine receptors located directly on cholinergic cells. The dopamine D5 receptor, a D1-class receptor subtype, potentiates acetylcholine release and has been investigated as a possible substrate underlying a variety of brain functions and clinical disorders. This receptor subtype, therefore, may prove to be a putative target for pharmacotherapeutic strategies and cognitive-behavioral treatments aimed at treating a variety of neurological disorders. The present study investigated whether cholinergic cells in the dopamine targeted areas of the cerebral cortex, striatum, basal forebrain, and diencephalon express the dopamine D5 receptor. These receptors were localized on cholinergic neurons with dual labeling immunoperoxidase or immunofluorescence procedures using antibodies directed against choline acetyltransferase (ChAT) and the dopamine D5 receptor. Results from this study support previous findings indicating that striatal cholinergic interneurons express the dopamine D5 receptor. In addition, cholinergic neurons in other critical brain areas also show dopamine D5 receptor expression. Dopamine D5 receptors were localized on the somata, dendrites, and axons of cholinergic cells in each of the brain areas examined. These findings support the functional importance of the dopamine D5 receptor in the modulation of acetylcholine release throughout the brain.
Keywords: Acetylcholine; Animals; Cholinergic Fibers; Diencephalon; Dopamine D5; Immunohistochemistry; Male; Neurons; Prosencephalon; Rats; Receptors; Sprague-Dawley; Tissue Distribution

Effect of ethanol on DARPP-32 phosphorylation in transgenic mice that express human type VII adenylyl cyclase in brain - Donohue, Timothy; Hoffman, Paula L.; Tabakoff, Boris (Alcoholism, Clinical and Experimental Research, 2005)
BACKGROUND: Dopamine and cyclic adenosine monophosphate-regulated phosphoprotein of molecular weight 32 kDa (DARPP-32) is a bidirectional signaling protein found in dopaminergically innervated brain areas. The characteristics and direction of DARPP-32 effects are regulated by phosphorylation of this protein. Phosphorylation of DARPP-32 on threonine-34 (T34) is regulated through the activation of dopamine (D1) receptors and stimulation of adenylyl cyclase (AC) and protein kinase A activity and by calcineurin. Phosphorylation of DARPP-32 on threonine-75 (T75) is regulated by cyclin-dependent kinase 5 and protein phosphatase 2A. DARPP-32 has been implicated in the motivational effects of ethanol. METHODS: The authors characterized transgenic mice that overexpress an ethanol-sensitive isoform of AC (AC7) in brain by measuring basal and ethanol-modulated DARPP-32 phosphorylation. Phosphorylated and total DARPP-32 were measured by immunoblotting in brain areas associated with the motivational and anxiolytic effects of ethanol (nucleus accumbens, striatum, and amygdala). RESULTS: AC7 transgenic mice had higher basal levels of T34 DARPP-32 than wild-type mice in striatum and amygdala, whereas basal levels of T75 DARPP-32 did not differ between wild-type and transgenic mice. Ethanol administration increased T34 DARPP-32 in nucleus accumbens and amygdala (but not in the striatum) of wild-type and transgenic mice (with a greater effect in amygdala of transgenic mice than wild-type mice). Ethanol administration increased T75 DARPP-32 in amygdala of only the wild-type mice and in nucleus accumbens and striatum of both the transgenic and wild-type mice. CONCLUSIONS: The effect of ethanol on the balance of DARPP-32 phosphorylation, especially in amygdala of wild-type versus transgenic mice, may contribute to differential motivational effects of ethanol in these animals.
Keywords: Adenylyl Cyclases; Animals; Brain; Central Nervous System Depressants; Dopamine and cAMP-Regulated Phosphoprotein 32; Ethanol; Humans; Immunoblotting; Inbred C57BL; Mice; Nerve Tissue Proteins; Nuclease Protection Assays; Phosphoproteins; Phosphorylation; Transgenic

Effects of ethanol drinking on central nervous system functional activity of alcohol-preferring rats - Sable, Helen J. K.; Rodd, Zachary A.; Bell, Richard L.; Schultz, Jonathan A.; Lumeng, Larry; McBride, William J. (Alcohol, 2005)
The [14C]-2-deoxyglucose (2-DG) technique was used to assess the rates of local cerebral glucose utilization (LCGU) in key limbic, cerebral cortical, hippocampal, basal ganglionic, and subcortical regions of alcohol-preferring (P) rats following chronic 24-h free-choice ethanol drinking. Adult male P rats were submitted to (1) 8 continuous weeks of two-bottle access to 15% ethanol and water (E-C group); (2) 8 weeks of identical two-bottle access followed by 2 weeks of ethanol deprivation (E-D group); (3) cycles of 2 weeks of two-bottle ethanol access and 2 weeks of deprivation, repeated for four cycles (E-RD group); or (4) water only treatment [ethanol-naive group (E-N group)]. A single pulse of [14C]-2-DG (125 μCi/kg) was administered via a venous catheter, and timed arterial blood samples were collected over 45 min and later assayed for plasma glucose and [14C]-2-DG concentrations. Quantitative autoradiography was used to determine [14C] densities, and LCGU values were calculated. With the exception of a few small differences in the hippocampus, no significant differences were found in any of the central nervous system (CNS) regions examined among the four experimental groups of P rats. Animals in the E-D group had lower LCGU rates in the anterior hippocampal CA1 subregion than animals in the E-N, E-C, and E-RD groups. In the anterior hippocampal CA3 subregion and the anterior hippocampal dentate gyrus, the E-D group had significantly lower LCGU rates than the E-RD group. Overall, the results of this study indicate that 24-h ethanol-drinking experience has little effect on CNS functional neuronal activity in P rats.
Keywords: Alcohol-deprivation effect; Alcohol-preferring (P) rats; Local cerebral glucose utilization; Quantitative autoradiography; [14C]-2-deoxyglucose

Endogenous kappa-opioid receptor systems regulate mesoaccumbal dopamine dynamics and vulnerability to cocaine - Chefer, Vladimir I.; Czyzyk, Traci; Bolan, Elizabeth A.; Moron, Jose; Pintar, John E.; Shippenberg, Toni S. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2005)
Genetic and pharmacological approaches were used to examine kappa-opioid receptor (KOR-1) regulation of dopamine (DA) dynamics in the nucleus accumbens and vulnerability to cocaine. Microdialysis revealed that basal DA release and DA extraction fraction (Ed), an indirect measure of DA uptake, are enhanced in KOR-1 knock-out mice. Analysis of DA uptake revealed a decreased Km but unchanged Vmax in knock-outs. Knock-out mice exhibited an augmented locomotor response to cocaine, which did not differ from that of wild-types administered a behavioral sensitizing cocaine treatment. The ability of cocaine to increase DA was enhanced in knock-outs, whereas c-fos induction was decreased. Although repeated cocaine administration to wild types produced behavioral sensitization, knock-outs exhibited no additional enhancement of behavior. Administration of the long-acting KOR antagonist nor-binaltorphimine to wild-type mice increased DA dynamics. However, the effects varied with the duration of KOR-1 blockade. Basal DA release was increased whereas Ed was unaltered after 1 h blockade. After 24 h, release and Ed were increased. The behavioral and neurochemical effects of cocaine were enhanced at both time points. These data demonstrate the existence of an endogenous KOR-1 system that tonically inhibits mesoaccumbal DA neurotransmission. Its loss induces neuroadaptations characteristic of "cocaine-sensitized" animals, indicating a critical role of KOR-1 in attenuating responsiveness to cocaine. The increased DA uptake after pharmacological inactivation or gene deletion highlights the plasticity of mesoaccumbal DA neurons and suggests that loss of KOR-1 and the resultant disinhibition of DA neurons trigger short- and long-term DA transporter adaptations that maintain normal DA levels, despite enhanced release.
Keywords: Analysis of Variance; Animal; Animals; Behavior; Blotting; Chromatography; Cocaine; dopamine; Dopamine Uptake Inhibitors; Dose-Response Relationship; Drug; Gene Expression; High Pressure Liquid; Immediate-Early Proteins; Inbred C57BL; kappa; Knockout; Linear Models; Mice; Microdialysis; Motor Activity; Nonlinear Dynamics; Nucleus Accumbens; Opioid; Receptors; Time Factors; Tritium; Western

Ethanol versus lipopolysaccharide-induced hypothermia: involvement of urocortin - Turek, V. F.; Ryabinin, A. E. (Neuroscience, 2005)
The urocortin1 (Ucn1) neurons of the mid-brain-localized Edinger-Westphal nucleus (EW) are robustly responsive to ethanol (EtOH) administration, and send projections to the dorsal raphe nucleus (DRN), which contains corticotropin-releasing factor type 2 receptors (CRF2) that are responsive to Ucn1. In addition, the DRN has been shown to be involved in regulation of body temperature, a function greatly affected by EtOH administration. The goal of the present study was to identify the role that the urocortinergic projections from the EW to the DRN have in mediating EtOH-induced and lipopolysaccharide (LPS)-induced hypothermia. Male C57BL6/J mice were used. Groups of mice underwent cannulation of the DRN, and then received i.p. injections of EtOH (2g/kg) or LPS (600 microg/kg or 400 microg/kg), followed by intra-DRN injections of artificial cerebrospinal fluid (aCSF) or anti-sauvagine (aSVG) (55 pmol), a CRF2 antagonist. Separate groups of mice received single intra-DRN injections of Ucn1 (20 pmol), CRF (20 pmol) or aCSF. For all experiments, core temperatures were monitored rectally every 30 min for several hours post-injection. Both EtOH and LPS induced hypothermia, and aSVG significantly attenuated this effect after EtOH; however, there was no significant attenuation of hypothermia after either dose of LPS. Ucn1 injection also caused hypothermia, while CRF injection did not. These data demonstrate that EtOH-induced hypothermia, but not LPS-induced hypothermia, may involve Ucn1 from EW acting at CRF2 receptors in the DRN.
Keywords: Amphibian Proteins; Analysis of Variance; Animals; Antibodies; Body Temperature; Corticotropin-Releasing Hormone; Dose-Response Relationship; Drug; Ethanol; Hypothermia; Inbred C57BL; Lipopolysaccharides; Male; Mesencephalon; Mice; Neural Pathways; Ochnaceae; Peptide Hormones; Peptides; Raphe Nuclei; Time Factors; Urocortins

Evaluation of a simple model of ethanol drinking to intoxication in C57BL/6J mice - Rhodes, Justin S.; Best, Karyn; Belknap, John K.; Finn, Deborah A.; Crabbe, John C. (Physiology & Behavior, 2005)
Because of intrinsic differences between humans and mice, no single mouse model can represent all features of a complex human trait such as alcoholism. It is therefore necessary to develop partial models. One important feature is drinking to the point where blood ethanol concentration (BEC) reaches levels that have measurable affects on physiology and/or behavior (>1.0 mg ethanol/ml blood). Most models currently in use examine relative oral self-administration from a bottle containing alcohol versus one containing water (two-bottle preference drinking), or oral operant self-administration. In these procedures, it is not clear when or if the animals drink to pharmacologically significant levels because the drinking is episodic and often occurs over a 24-h period. The aim of this study was to identify the optimal parameters and evaluate the reliability of a very simple procedure, taking advantage of a mouse genotype (C57BL/6J) that is known to drink large quantities of ethanol. We exchanged for the water bottle a solution containing ethanol in tap water for a limited period, early in the dark cycle, in the home cage. Mice regularly drank sufficient ethanol to achieve BEC>1.0 mg ethanol/ml blood. The concentration of ethanol offered (10%, 20% or 30%) did not affect consumption in g ethanol/kg body weight. The highest average BEC ( approximately 1.6 mg/ml) occurred when the water-to-ethanol switch occurred 3 h into the dark cycle, and when the ethanol was offered for 4 rather than 2 h. Ethanol consumption was consistent within individual mice, and reliably predicted BEC after the period of ethanol access. C57BL/6J mice from three sources provided equivalent data, while DBA/2J mice drank much less than C57BL/6J in this test. We discuss advantages of the model for high-throughput screening assays where the goal is to find other genotypes of mice that drink excessively, or to screen drugs for their efficacy in blocking excessive drinking.
Keywords: Alcohol Drinking; Alcoholic Intoxication; Animal; Animals; Behavior; Central Nervous System Depressants; Disease Models; Dose-Response Relationship; Drinking Behavior; Drug; Ethanol; Female; Inbred C57BL; Male; Mice; Reproducibility of Results; Time Factors

Expression of c-Fos in the mouse Edinger–Westphal nucleus following ethanol administration is not secondary to hypothermia or stress - Turek, Victoria F.; Ryabinin, Andrey E. (Brain Research, 2005)
Restraint stress, lipopolysaccharide (LPS), and ethanol (EtOH) administration have all been found to induce c-Fos in the brain, and to cause hypothermia. The present study was designed to assess whether the c-Fos expression that occurs in the Edinger–Westphal nucleus (EW) after EtOH administration is independent of the hypothermia or any stress effects that occur. To test this, we used restraint stress and LPS in addition to EtOH, and also examined two control areas, the dorsal raphe nucleus (DRN) and the periaqueductal gray (PAG), in addition to EW. Male C57BL6/J mice were used. Groups of mice received intraperitoneal (IP) injections of EtOH (2 g/kg), LPS (600 μg/kg or 50 μg/kg), or saline. A separate group of mice received no injection, but were placed in plastic restrainers for the entirety of the experiment. For all groups, core temperatures were monitored rectally every 30 min for 3 h postinjection, after which, the animals were sacrificed. Then, the number of Fos-positive cells in the brain regions of the EW, DRN, and PAG was quantified. Both EtOH and restraint stress induced a transient hypothermia, where core temperature (Tc) declined immediately and then rose again. Both doses of LPS induced a slower developing, longer lasting hypothermia, while saline had no effect on Tc. Only EtOH induced a significant amount of c-Fos in EW, while both doses of LPS and restraint stress induced c-Fos in DRN, and only restraint stress caused induction in PAG. These data demonstrate that activation of EW after EtOH is unrelated to hypothermia or stress.
Keywords: Dorsal raphe; Lipopolysaccharide; Periaqueductal gray; Restraint; Temperature

Expression Profiling in Alcoholism Research - Bergeson, Susan E.; Berman, Ari E.; Dodd, Peter R.; Edenberg, Howard J.; Hitzemann, Robert J.; Lewohl, Joanne M.; Lodowski, Kerrie H.; Sommer, Wolfgang H. (Alcoholism, clinical and experimental research, 2005)
This article represents the proceedings of a symposium at the 2004 International Society for Biomedical Research on Alcoholism in Mannheim, Germany, organized and co-chaired by Susan E. Bergeson and Wolfgang Sommer. The presentations and presenter were (1) Gene Expression in Brains of Alcohol-Preferring and Non-Preferring Rats, by Howard J. Edenberg (2) Candidate Treatment Targets for Alcoholism: Leads from Functional Genomics Approaches, by Wolfgang Sommer (3) Microarray Analysis of Acute and Chronic Alcohol Response in Brain, by Susan E. Bergeson (4) On the Integration of QTL and Gene Expression Analysis, by Robert J. Hitzemann (5) Microarray and Proteomic Analysis of the Human Alcoholic Brain, by Peter R. Dodd.

Gene expression in animals with different acute responses to ethanol - Hoffman, Paula; Tabakoff, Boris (Addiction Biology, 2005)
The genetic and environmental contributions to differences in response to ethanol have been examined widely using inbred strains, selected lines and genetically engineered (transgenic and 'knock-out') animals. In addition, recombinant inbred strains have been used to identify QTLs (chromosomal regions) associated with particular responses to ethanol. If the polymorphism that underlies such a QTL is localized within the regulatory region of a gene, it could alter the level or stability of the gene product (transcript). This possibility can be addressed by measuring mRNA levels in brains (or other tissue) of inbred or selected lines of animals using DNA microarray technology. In this paper, we review microarray studies conducted in animals that differ in their responses to ethanol. The results of these studies point out the critical nature of the experimental design, statistical analyses and 'filtering' procedures for producing interpretable data and identifying candidate genes. In particular, the determination of differentially expressed genes between selected lines of animals, and the localization of the differentially expressed genes within QTLs for the selected phenotype, dramatically increases the probability of identifying genes that contribute to that phenotype through differential expression. Microarray analysis can also be used to assess changes in gene expression that accompany transgene introduction and/or gene 'knock-out', which may modulate the influence of the targeted gene on behaviour.
Keywords: Animals; Brain; Cell Line; Central Nervous System Depressants; Dose-Response Relationship; Drug; Drug Tolerance; Ethanol; Female; Gene Expression; Male; Messenger; Mice; N-Methyl-D-Aspartate; Oligonucleotide Array Sequence Analysis; Phenotype; Phosphorylation; Quantitative Trait Loci; Receptors; Reverse Transcriptase Polymerase Chain Reaction; RNA

Gene expression in the hippocampus of inbred alcohol-preferring and -nonpreferring rats - Edenberg, H. J.; Strother, W. N.; McClintick, J. N.; Tian, H.; Stephens, M.; Jerome, R. E.; Lumeng, L.; Li, T.-K.; McBride, W. J. (Genes, Brain, and Behavior, 2005)
The hippocampus is sensitive to the effects of ethanol and appears to have a role in the development of alcohol tolerance. The objective of this study was to test the hypothesis that there are innate differences in gene expression in the hippocampus of inbred alcohol-preferring (iP) and -nonpreferring (iNP) rats that may contribute to differences in sensitivity to ethanol and/or in the development of tolerance. Affymetrix microarrays were used to measure gene expression in the hippocampus of alcohol-naive male iP and iNP rats in two experiments (n=4 and 6 per strain in the two experiments). Combining data from the two experiments, there were 137 probesets representing 129 genes that significantly differed (P < or = 0.01); 62 probesets differed at P < or = 0.001. Among the 36% of the genes that were expressed more in the iP than iNP rat at this level of significance, many were involved in cell growth and adhesion, cellular stress reduction and anti-oxidation, protein trafficking, regulation of gene expression, synaptic function and metabolism. Among the 64% of the genes that had lower expression in the hippocampus of iP than iNP rats were genes involved in metabolic pathways, cellular signaling systems, protein trafficking, cell death and neurotransmission. Overall, the data indicate that there are significant innate differences in gene expression in the hippocampus between iP and iNP rats, some of which might contribute to the differences observed in the development of alcohol tolerance between the selectively bred P and NP lines.
Keywords: Alcohol Drinking; Animals; Chromosome Mapping; Ethanol; Food Preferences; Gene Expression Profiling; Hippocampus; Inbred Strains; Male; Messenger; Oligonucleotide Array Sequence Analysis; Rats; RNA; Species Specificity; Taste

Gene expression induced by drugs of abuse - Rhodes, Justin S.; Crabbe, John C. (Current Opinion in Pharmacology, 2005)
The transition from infrequent drug use to addiction (i.e. the loss of control over consumption of a drug) probably involves changes in gene expression that restructure neural circuits in the brain. The number of genes that have been demonstrated to change expression in response to drugs has increased rapidly in recent years owing to microarray technology, which allows measurement of thousands of genes at one time. It is now important to identify which of these changes are causally related to the compulsive behavior associated with drug addiction, and which are non-specific changes related to general features of arousal or other physiological responses (e.g. stress, altered body temperature or energy metabolism).
Keywords: Animal; Animals; Disease Models; Humans; Oligonucleotide Array Sequence Analysis; Signal Transduction; Street Drugs; Substance-Related Disorders

Homer2 is necessary for EtOH-induced neuroplasticity - Szumlinski, Karen K.; Lominac, Kevin D.; Oleson, Erik B.; Walker, Jennifer K.; Mason, Ashley; Dehoff, Marlin H.; Klugmann, Matthias; Klugman, Matthias; Cagle, Stephanie; Welt, Kristine; During, Matthew; Worley, Paul F.; et al. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2005)
Homer proteins are integral to the assembly of proteins regulating glutamate signaling and synaptic plasticity. Constitutive Homer2 gene deletion [knock-out (KO)] and rescue with adeno-associated viral (AAV) transfection of Homer2b was used to demonstrate the importance of Homer proteins in neuroplasticity produced by repeated ethanol (EtOH) administration. Homer2 KO mice avoided drinking high concentrations of EtOH and did not develop place preference or locomotor sensitization after repeated EtOH administration. The deficient behavioral plasticity to EtOH after Homer2 deletion was paralleled by a lack of augmentation in the rise in extracellular dopamine and glutamate elicited by repeated EtOH injections. The genotypic differences in EtOH-induced change in behavior and neurochemistry were essentially reversed by AAV-mediated transfection of Homer2b into accumbens cells including, differences in EtOH preference, locomotor sensitization, and EtOH-induced elevations in extracellular glutamate and dopamine. These data demonstrate a necessary and active role for accumbens Homer2 expression in regulating EtOH-induced behavioral and cellular neuroplasticity.
Keywords: Alcohol Drinking; Animals; Avoidance Learning; Carrier Proteins; Central Nervous System Depressants; Drug Synergism; Ethanol; Excitatory Amino Acid Antagonists; Female; Gene Deletion; Homer Scaffolding Proteins; Inbred C57BL; Knockout; Male; Mice; N-Methyl-D-Aspartate; Neuronal Plasticity; Nucleus Accumbens; Piperazines; Receptors; Reflex

Hybrid C57BL/6J x FVB/NJ mice drink more alcohol than do C57BL/6J mice - Blednov, Yuri A.; Metten, Pamela; Finn, Deborah A.; Rhodes, Justin S.; Bergeson, Susan E.; Harris, R. Adron; Crabbe, John C. (Alcoholism, Clinical and Experimental Research, 2005)
BACKGROUND: From several recent strain surveys (28 strains: Bachmanov et al., personal communication; 22 strains: Finn et al., unpublished), and from data in >100 other published studies of 24-hr two-bottle ethanol preference, it is known that male C57BL/6 (B6) mice self-administer about 10-14 g/kg/day and that female B6 mice self-administer about 12-18 g/kg/day. No strain has been found to consume more ethanol than B6. In one of our laboratories (Texas), we noted a markedly greater intake of ethanol in an F1 hybrid of B6 and FVB/NJ (FVB) mice. METHODS: To confirm and extend this finding, we repeated the study at another site (Portland) using concentrations up to 30% ethanol and also tested B6xFVB F1 mice in restricted access drinking procedures that produce high levels of alcohol intake. RESULTS: At both sites, we found that B6xFVB F1 mice self-administered high levels of ethanol during two-bottle preference tests (females averaging from 20 to 35 g/kg/day, males 7-25 g/kg/day, depending on concentration). F1 hybrids of both sexes drank significantly more 20% ethanol than both the B6 and FVB strains. Female F1 hybrids also drank more 30% ethanol. In the restricted access tests, ethanol consumption in the F1 hybrids was equivalent to that in B6 mice. CONCLUSIONS: These data show that this new genetic model has some significant advantages when compared to existing inbred strains, and could be used to explore the genetic basis of high ethanol drinking in mice.
Keywords: Alcohol Drinking; Animals; Conditioning; Ethanol; Female; Genetic; Hybridization; Inbred C57BL; Inbred Strains; Male; Mice; Models; Operant; Self Administration; Sex Factors; Species Specificity

Isolation of mRNA from specific tissues of Drosophila by mRNA tagging - Yang, Zhiyong; Edenberg, Howard J.; Davis, Ronald L. (Nucleic Acids Research, 2005)
To study the function of specific cells or tissues using genomic tools like microarray analyses, it is highly desirable to obtain mRNA from a homogeneous source. However, this is particularly challenging for small organisms, like Caenorhabditis elegans and Drosophila melanogaster. We have optimized and applied a new technique, mRNA tagging, to isolate mRNA from specific tissues of D.melanogaster. A FLAG-tagged poly(A)-binding protein (PABP) is expressed in a specific tissue and mRNA from that tissue is thus tagged by the recombinant PABP and separated from mRNA in other tissues by co-immunoprecipitation with a FLAG-tag specific antibody. The fractionated mRNA is then amplified and used as probe in microarray experiments. As a test system, we employed the procedures to identify genes expressed in Drosophila photoreceptor cells. We found that most known photoreceptor cell-specific mRNAs were identified by mRNA tagging. Furthermore, at least 11 novel genes have been identified as enriched in photoreceptor cells. mRNA tagging is a powerful general method for profiling gene expression in specific tissues and for identifying tissue-specific genes.

Laboratory models of alcoholism: treatment target identification and insight into mechanisms - Lovinger, David M.; Crabbe, John C. (Nature Neuroscience, 2005)
Laboratory models, including animal tissues and live animals, have proven useful for discovery of molecular targets of alcohol action as well as for characterization of genetic and environmental factors that influence alcohol's neural actions. Here we consider strengths and weaknesses of laboratory models used in alcohol research and analyze the limitations of using animals to model a complex human disease. We describe targets for the neural actions of alcohol, and we review studies in which animal models were used to examine excessive alcohol drinking and to discover genes that may contribute to risk for alcoholism. Despite some limitations of the laboratory models used in alcohol research, these experimental approaches are likely to contribute to the development of new therapies for alcohol abuse and alcoholism.
Keywords: alcoholism; Animal; Animals; Biological; Disease Models; Environment; Genetic; Genetic Predisposition to Disease; Humans; Models

Lack of stimulant and anxiolytic-like effects of ethanol and accelerated development of ethanol dependence in mu-opioid receptor knockout mice - Ghozland, Sandy; Chu, Kathleen; Kieffer, Brigitte L.; Roberts, Amanda J. (Neuropharmacology, 2005)
The opioid system is implicated in various aspects of alcoholism. Acute ethanol administration produces anxiolytic-like effects in rodents while alcohol withdrawal induces anxiogenic-like effects. Mice lacking the mu-opioid receptor (MOR) do not self-administer ethanol and display decreased anxiety-like behavior. We hypothesized that MOR might be involved in the development and expression of alcoholism, particularly in relation to anxiety states. In mice lacking MOR (MOR-/- mice), we examined the acute anxiolytic-like and locomotor stimulant effects of ethanol (0, 0.75, 1.25, 1.75 g/kg, i.p.). In a separate experiment, mice were submitted to chronic ethanol-containing liquid diet and we assessed somatic and affective ethanol withdrawal on three consecutive withdrawal episodes by scoring handling-induced convulsions and anxiety-like behavior. Deletion of MOR blocked the acute anxiolytic-like and stimulant effects of ethanol. Furthermore, MOR-/- mice displayed affective and physical signs of ethanol withdrawal in earlier withdrawal tests than wild-type mice. The present results implicate MOR in affective and somatic aspects of ethanol exposure and withdrawal. In addition, our findings support the hypothesis that the clinical efficacy of the opioid receptor antagonist naltrexone against relapse to alcoholism might be related to an action on the acute positive effects of alcohol rather than the negative affect of abstinence.
Keywords: Alcohol Drinking; Analysis of Variance; Animals; Central Nervous System Depressants; Dose-Response Relationship; Drug; Ethanol; Inbred C57BL; Knockout; Male; Mice; Motor Activity; mu; Opioid; Receptors; Substance Withdrawal Syndrome; Substance-Related Disorders

Lesions of the Edinger-Westphal nucleus alter food and water consumption - Weitemier, Adam Z.; Ryabinin, Andrey E. (Behavioral Neuroscience, 2005)
The Edinger-Westphal nucleus (EW) produces several neuropeptides, including urocortin 1 and cocaine-amphetamine-regulated transcript, which regulate feeding, energy balance, and anxiety. Additionally, the EW projects to feeding and anxiety-regulatory brain areas. The authors tested the effect of lesions of the EW on the consumption of food, water and flavored solutions, metabolic indices, and exploratory behavior on the elevated plus maze in male C57BL/6J mice. EW lesion significantly reduced basal and deprivation-induced food and fluid consumption compared with sham and placement controls, but it did not alter behavior on the elevated plus maze. EW lesion had no effect on indices of basal metabolic activity, including plasma glucose level and body temperature. These effects suggest that the peptidergic neurons of the EW regulate food consumption.
Keywords: Animal; Animals; Behavior; Blood Glucose; Body Temperature; Body Weight; Corticosterone; Drinking; Eating; Exploratory Behavior; Food Deprivation; Immunohistochemistry; Inbred C57BL; Male; Maze Learning; Mice; Reaction Time; Saccharin; Sodium Chloride; Tegmentum Mesencephali; Time Factors

Male transgenic glycine receptor alpha1 (S267Q) mutant mice display a hyperekplexia-like increase in acoustic startle responses - Findlay, G. S.; Harris, R. A.; Blednov, Y. A. (Pharmacology, Biochemistry, and Behavior, 2005)
Glycine receptors (GlyR) are ligand-gated ion channels that inhibit neurotransmission in the spinal cord and brainstem, and mutations in GlyR can cause the human disease hyperekplexia, which is characterized by elevated startle responses. Recently, the GlyR alpha1S267Q mutation was shown to disrupt normal GlyR function, and knock-in mice harboring this mutation displayed profoundly increased acoustic startle responses and reduced glycine-stimulated the chloride flux [Findlay, G.S., Phelan, R., Roberts, M.T., Homanics, G.E., Bergeson, S.E., Lopreato, G.F., Mihic, S.J., Blednov, Y.A., Harris, R.A. 2003. Glycine receptor knock-in mice and hyperekplexia: comparisons with the null mutant. J Neurosci 23, 8051-8059.]. In this study, a transgenic mouse model expressing this S267Q mutation was evaluated using similar techniques to determine if these mice are similarly affected. Male transgenic mice displayed increased acoustic startle responses. However, decreases in glycine-stimulated strychnine-sensitive radioactive chloride (36Cl-) uptake were not observed in spinal cord and brainstem synaptoneurosomes from transgenic mice. No changes in habituation or prepulse inhibition of startle responses or spontaneous locomotion in response to taurine were observed as a result of presence of the transgene. Consistent with previous studies using immunoblotting and strychnine binding [Findlay, G.S., Wick, M.J., Mascia, M.P., Wallace, D., Miller, G.W., Harris, R.A., Blednov, Y.A. 2002. Transgenic expression of a mutant glycine receptor decreases alcohol sensitivity of mice. J Pharmacol Exp Ther 300, 526-534.], the glycine-stimulated strychnine-sensitive chloride flux of cortical microsacs in transgenic mice confirmed the ectopic expression of transgenic GlyR. These results support both the idea that transgenic expression of the S267Q mutation produces a less dramatic phenotype as compared to the knock-in mouse model as well as the idea that the in vivo acoustic startle test (as compared to the in vitro chloride flux assay) is particularly sensitive to disruptions in GlyR function.
Keywords: Animals; Glycine; Locomotion; Male; Mice; Receptors; Reflex; Startle; Taurine; Transgenic

Mapping DNA-protein interactions in large genomes by sequence tag analysis of genomic enrichment - Kim, Jonghwan; Bhinge, Akshay A.; Morgan, Xochitl C.; Iyer, Vishwanath R. (Nature Methods, 2005)
Identifying the chromosomal targets of transcription factors is important for reconstructing the transcriptional regulatory networks underlying global gene expression programs. We have developed an unbiased genomic method called sequence tag analysis of genomic enrichment (STAGE) to identify the direct binding targets of transcription factors in vivo. STAGE is based on high-throughput sequencing of concatemerized tags derived from target DNA enriched by chromatin immunoprecipitation. We first used STAGE in yeast to confirm that RNA polymerase III genes are the most prominent targets of the TATA-box binding protein. We optimized the STAGE protocol and developed analysis methods to allow the identification of transcription factor targets in human cells. We used STAGE to identify several previously unknown binding targets of human transcription factor E2F4 that we independently validated by promoter-specific PCR and microarray hybridization. STAGE provides a means of identifying the chromosomal targets of DNA-associated proteins in any sequenced genome.
Keywords: Cells; Chromatin Immunoprecipitation; Cultured; DNA; DNA Primers; DNA-Binding Proteins; E2F4 Transcription Factor; Genetic; Genetic Techniques; Genome; Humans; Immunoprecipitation; Nucleic Acid Hybridization; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Promoter Regions; Protein Binding; Transcription; Transcription Factors

Murine models of substance and alcohol dependence: Unraveling genetic complexities - Cronise, Kim; Crabbe, John C. (2005)

Neuroactive steroids and ethanol - Purdy, Robert H.; Valenzuela, C. Fernando; Janak, Patricia H.; Finn, Deborah A.; Biggio, Giovanni; Bäckström, Torbjörn (Alcoholism: Clinical and Experimental Research, 2005)

Neuroimaging of rodent and primate models of alcoholism: initial reports from the integrative neuroscience initiative on alcoholism - Sullivan, Edith V.; Sable, Helen J. K.; Strother, Wendy N.; Friedman, David P.; Davenport, April; Tillman-Smith, Heather; Kraft, Robert A.; Wyatt, Christopher; Szeliga, Kendall T.; Buchheimer, Nancy C.; Daunais, James B.; Adalsteinsson, Elfar; et al. (Alcoholism, Clinical and Experimental Research, 2005)
Neuroimaging of animal models of alcoholism offers a unique path for translational research to the human condition. Animal models permit manipulation of variables that are uncontrollable in clinical, human investigation. This symposium, which took place at the annual meeting of the Research Society on Alcoholism in Vancouver, British Columbia, Canada, on June 29th, 2004, presented initial findings based on neuroimaging studies from the two centers of the Integrative Neuroscience Initiative on Alcoholism funded by the National Institute on Alcohol Abuse and Alcoholism. Effects of alcohol exposure were assessed with in vitro glucose metabolic imaging of rat brain, in vitro receptor imaging of monkey brain, in vivo magnetic resonance imaging of monkey brain, and in vivo magnetic resonance spectroscopic quantification of alcohol metabolism kinetics in rat brain.
Keywords: alcoholism; Animal; Animals; Diagnostic Imaging; Disease Models; Macaca fascicularis; Magnetic Resonance Spectroscopy; Rats

Neurosteroid Modulators of GABAA Receptors Differentially Modulate Ethanol Intake Patterns in Male C57BL/6J Mice - Ford, Matthew M.; Nickel, Jeffrey D.; Phillips, Tamara J.; Finn, Deborah A. (Alcoholism, clinical and experimental research, 2005)
Background Allopregnanolone (ALLO) and structurally related endogenous neurosteroids are potent modulators of GABAA receptor function at physiologically relevant concentrations. Accumulating evidence implicates a modulatory role for ALLO in behavioral processes underlying ethanol self-administration, discrimination and reinstatement. The purpose of this study was to evaluate the impact of exogenous neurosteroid challenges with the agonist ALLO and the partial agonist/antagonist epipregnanolone (EPI) on the microarchitecture of ethanol drinking patterns. Methods Male C57BL/6J mice were initiated to consume an unsweetened 10% v/v ethanol solution (10E) by a saccharin fading procedure during daily 2-hour limited access sessions beginning 1 hour after dark phase onset. Cumulative lick responses were recorded for 10E and water using lickometer circuits. After establishing 10E intake baselines, mice were habituated to vehicle injection (VEH; 20% w/v β-cyclodextrin; i.p.), and then were treated with either VEH or neurosteroid immediately prior to the drinking session. Each mouse received a series of ALLO doses (3.2, 10, 17 and 24 mg/kg) alone and EPI doses (0.15, 1, 3 and 10 mg/kg) alone in a counterbalanced within-group design. Results The GABAA receptor positive modulator, ALLO, dose-dependently modulated overall ethanol intake throughout the 2-hr session with the 3.2 mg/kg dose eliciting a significant increase whereas the 24 mg/kg dose produced a significant suppression of ethanol intake versus vehicle pretreatment. ALLO-evoked alterations in intake corresponded with a significant, dose-dependent alterations in bout frequency and inter-bout interval. ALLO also elicited robust, dose-dependent elevations in 10E licks during the initial 5-minutes of access, but subsequently resulted in a dose-dependent suppression of 10E licks during session minutes 20–80. In contrast, the partial agonist/antagonist neurosteroid, EPI, exhibited no influence on any consumption parameter evaluated. Conclusions The present findings suggest that GABAA receptor-active neurosteroids may modulate the regulatory processes that govern the onset, maintenance, and termination of drinking episodes. The differential influence of ALLO and EPI on ethanol intake patterns may reflect an alteration in GABAergic inhibitory tone that is likely due to each neurosteroid’s pharmacological profile at GABAA receptors. Manipulation of endogenous ALLO may prove a useful strategy for diminishing excessive intake and protecting against the loss of regulatory control over drinking.

Nicotine addiction and comorbidity with alcohol abuse and mental illness - Dani, John A.; Harris, R. Adron (Nature Neuroscience, 2005)
The World Health Organization estimates that one-third of the global adult population smokes. Because tobacco use is on the rise in developing countries, death resulting from tobacco use continues to rise. Nicotine, the main addictive component of tobacco, initiates synaptic and cellular changes that underlie the motivational and behavioral alterations that culminate in addiction. Nicotine addiction progresses rapidly in adolescents and is most highly expressed in vulnerable people who have psychiatric illness or other substance abuse problems.
Keywords: alcoholism; Biological; Comorbidity; Humans; limbic system; Mental Disorders; Models; Reward; Tobacco Use Disorder

Pathobiology of dynorphins in trauma and disease - Hauser, Kurt F.; Aldrich, Jane V.; Anderson, Kevin J.; Bakalkin, Georgy; Christie, MacDonald J.; Hall, Edward D.; Knapp, Pamela E.; Scheff, Stephen W.; Singh, Indrapal N.; Vissel, Bryce; Woods, Amina S.; Yakovleva, Tatiana; et al. (Frontiers in Bioscience: A Journal and Virtual Library, 2005)
Dynorphins, endogenous opioid neuropeptides derived from the prodynorphin gene, are involved in a variety of normative physiologic functions including antinociception and neuroendocrine signaling, and may be protective to neurons and oligodendroglia via their opioid receptor-mediated effects. However, under experimental or pathophysiological conditions in which dynorphin levels are substantially elevated, these peptides are excitotoxic largely through actions at glutamate receptors. Because the excitotoxic actions of dynorphins require supraphysiological concentrations or prolonged tissue exposure, there has likely been little evolutionary pressure to ameliorate the maladaptive, non-opioid receptor mediated consequences of dynorphins. Thus, dynorphins can have protective and/or proapoptotic actions in neurons and glia, and the net effect may depend upon the distribution of receptors in a particular region and the amount of dynorphin released. Increased prodynorphin gene expression is observed in several disease states and disruptions in dynorphin processing can accompany pathophysiological situations. Aberrant processing may contribute to the net negative effects of dysregulated dynorphin production by tilting the balance towards dynorphin derivatives that are toxic to neurons and/or oligodendroglia. Evidence outlined in this review suggests that a variety of CNS pathologies alter dynorphin biogenesis. Such alterations are likely maladaptive and contribute to secondary injury and the pathogenesis of disease.
Keywords: Animals; Apoptosis; Dynorphins; Evolution; Gene Expression Regulation; Humans; Molecular; Neuroglia; Neurons; Neuropeptides; Opioid; Receptors; Spinal Cord Injuries

Patterns of brain activation associated with contextual conditioning to methamphetamine in mice - Rhodes, Justin S.; Ryabinin, Andrey E.; Crabbe, John C. (Behavioral Neuroscience, 2005)
Classical conditioning is thought to play a key role in addiction. The authors used c-Fos immunohistochemistry to demonstrate a conditioned physiological response to methamphetamine (meth) in mice. Male outbred mice were placed into an environment where they had previously experienced 2 mg/kg meth or saline. The meth-paired mice displayed increased c-Fos in several brain regions, including the nucleus accumbens, prefrontal cortex, orbitofrontal cortex, basolateral amygdala, and bed nucleus of the stria terminalis. No conditioned locomotor activity was observed, but individual activity levels strongly correlated with c-Fos in many regions. A batch effect among immunohistochemical assays was demonstrated. Results implicate specific brain regions in classical conditioning to meth and demonstrate the importance of considering locomotor activity and batch in a c-Fos study.
Keywords: Analysis of Variance; Animal; Animals; Behavior; Brain; Brain Mapping; Cell Count; Central Nervous System Stimulants; Classical; Conditioning; Immunohistochemistry; Male; Methamphetamine; Mice; Motor Activity; Proto-Oncogene Proteins c-fos; Time Factors

Perturbation of chemokine networks by gene deletion alters the reinforcing actions of ethanol - Blednov, Yuri A.; Bergeson, Susan E.; Walker, Danielle; Ferreira, Vania M. M.; Kuziel, William A.; Harris, R. Adron (Behavioural Brain Research, 2005)
Microarray analysis of human alcoholic brain and cultured cells exposed to ethanol showed significant changes in expression of genes related to immune or inflammatory responses, including chemokines and chemokine receptors. To test the hypothesis that chemokines exhibit previously undiscovered pleiotropic effects important for the behavioral actions of ethanol, we studied mutant mice with deletion of the Ccr2, Ccr5, Ccl2 or Ccl3 genes. Deletion of Ccr2, Ccl2 (females) or Ccl3 in mice resulted in lower preference for alcohol and consumption of lower amounts of alcohol in a two-bottle choice test as compared with wild-type mice. Ethanol treatment (2.5 g/kg, i.p.) induced stronger conditioned taste aversion in Ccr2, Ccl2 or Ccl3 null mutant mice than in controls. Ccr2 and Ccr5 null mutant mice did not differ from wild-type mice in ethanol-induced loss of righting reflex (LORR), but mice lacking Ccl2 or Ccl3 showed longer LORR than wild-type mice. There were no differences between mutant strains and wild-type mice in severity of ethanol-induced withdrawal. Genetic mapping of chromosome 11 for the Ccl2 and Ccl3 genes (46.5 and 47.6 cM, respectively) revealed that an alcohol-induced LORR QTL region was contained within the introgressed region derived from 129/SvJ, which may cause some behavioral phenotypes observed in the null mice. On the contrary, known QTLs on Chr 9 are outside of 129/SvJ region in Ccr2 and Ccr5 (71.9 and 72.0 cM, respectively) null mutant mice. These data show that disruption of the chemokine network interferes with motivational effects of alcohol.
Keywords: Chemokines; Conditioned taste aversion; Ethanol; Intake; Knockout mice

Platelet serotonin uptake and paroxetine binding among allelic genotypes of the serotonin transporter in alcoholics - Javors, Martin A.; Seneviratne, Chamindi; Roache, John D.; Ait-Daoud, Nassima; Bergeson, Susan E.; Walss-Bass, M. Consuelo; Akhtar, Fatema Z.; Johnson, Bankole A. (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2005)
{Expression rates of long (L) and short (S) alleles of the serotonin (5-HT) transporter (5-HTT) gene have been shown to differ under various circumstances. We compared 5-HTT uptake (function) level and paroxetine binding (density) in platelets of alcoholics as indices of 5-HTT expression rate among LL, LS, and SS genotypes. Concentration curves of [3H]5-HT and [3H]paroxetine were used to quantify the equilibrium constant (Km) and maximum 5-HT uptake rate (Vmax) for 5-HTT uptake into intact platelets and the dissociation constant (Kd) and maximum specific binding density (Bmax) for paroxetine binding to platelet membranes, respectively. Genotypes were determined using electrophoresis with fluorescent markers. Vmax for 5-HTT uptake did not correlate with Bmax for paroxetine binding (r=-0.095
Keywords: Adult; alcoholism; Alleles; Blood Platelets; Cell Membrane; Female; Genetic; Genotype; Humans; Kinetics; Male; Membrane Glycoproteins; Membrane Transport Proteins; Nerve Tissue Proteins; Paroxetine; Polymorphism; Serotonin; Serotonin Plasma Membrane Transport Proteins; Serotonin Uptake Inhibitors

A procedure to produce high alcohol intake in mice - Finn, Deborah A.; Belknap, John K.; Cronise, Kim; Yoneyama, Naomi; Murillo, Andrea; Crabbe, John C. (Psychopharmacology, 2005)
RATIONALE: While prolonged access to ethanol (EtOH), or deprivations, or their combination have occasionally been shown to yield high levels of voluntary self-administration, in almost all cases, rodents do not self-administer alcohol to the degree that they will develop substantial, intoxicating blood alcohol levels and then continue to self-administer at these levels. OBJECTIVES: The purpose of the present series of experiments was to modify a fluid restriction procedure to demonstrate consistent, high EtOH consumption. METHODS: Male and female mice from an alcohol preferring inbred strain (C57BL/6J; B6) as well as from a genetically heterogeneous strain (WSC) were given varying periods of access to fluid, ranging from 90 min to 10 h per day, for 12-21 days. Every 3rd or 4th day, separate groups of mice were offered a 5, 7 or 10% EtOH solution for either 10 min or 30 min, followed by water for the remainder of the time. RESULTS: In all studies, stable high EtOH doses were consumed by both B6 and WSC mice across the EtOH sessions, exceeding 2 g/kg in a 30-min session. Mean blood EtOH concentration exceeded 1 mg/ml (i.e. 100 mg%), with values in individual animals ranging from 0.6 mg/ml to 3.4 mg/ml. Notably, mice receiving 10 h of fluid/day continued to consume 2 g/kg doses of EtOH. While this procedure did not produce subsequent preference for EtOH in WSC mice, consumption remained high in some animals. CONCLUSIONS: These data indicate that scheduling fluid intake produces high, stable EtOH consumption and BEC in male and female B6 and WSC mice.
Keywords: Administration; Alcohol Drinking; Animal; Animals; Body Weight; Disease Models; Drinking; Drug Administration Schedule; Ethanol; Female; Genotype; Inbred Strains; Male; Mice; Oral; Psychopharmacology; Solutions; Species Specificity; Time Factors; Water

Prolonged Increase in the Sensitivity of the Posterior Ventral Tegmental Area to the Reinforcing Effects of Ethanol following Repeated Exposure to Cycles of Ethanol Access and Deprivation - Rodd, Zachary A.; Bell, Richard L.; McQueen, Victoria K.; Davids, Michelle R.; Hsu, Cathleen C.; Murphy, James M.; Li, Ting-Kai; Lumeng, Lawrence; McBride, William J. (The Journal of pharmacology and experimental therapeutics, 2005)
The posterior ventral tegmental area (VTA) is a neuroanatomical substrate mediating the reinforcing effects of ethanol in rats. Repeated alcohol deprivations produce robust ethanol intakes of alcohol-preferring (P) rats during relapse and increase the reinforcing effects of oral alcohol self-administration. The objective of this study was to test the hypothesis that alcohol drinking and repeated alcohol deprivations will increase the reinforcing effects of ethanol within the posterior VTA of P rats. Groups of female P rats were used (alcohol-naive, continuous access, and repeatedly deprived). Each rat was implanted with a guide cannula aimed at the posterior VTA. Depression of the active lever produced the infusion of 100 nl of artificial cerebrospinal fluid (CSF) or ethanol (25–300 mg%). Each rat was given only one ethanol concentration during the 4-h sessions conducted every other day. Compared with the infusions of artificial CSF, the alcohol-naive group reliably self-infused 75 and 150 mg% ethanol, but not the lower or higher concentrations. On the other hand, the continuous access group had significantly higher self-infusions of 50, 75, 150, and 300 mg% ethanol compared with artificial CSF infusions. The repeatedly deprived group also self-infused significantly more of 50, 75, 150, and 300 mg% ethanol than artificial CSF; moreover, the number of infusions for all four concentrations was higher in the repeatedly deprived versus the continuous access group. Chronic alcohol drinking by P rats increased the reinforcing effects of ethanol within the posterior VTA, and repeated alcohol deprivations produced a further increase in these reinforcing effects of ethanol.

A proteomic survey of rat cerebral cortical synaptosomes - Witzmann, Frank A.; Arnold, Randy J.; Bai, Fengju; Hrncirova, Petra; Kimpel, Mark W.; Mechref, Yehia S.; McBride, William J.; Novotny, Milos V.; Pedrick, Nathan M.; Ringham, Heather N.; Simon, Jay R. (Proteomics, 2005)
Previous findings from our laboratory and others indicate that two-dimensional gel electrophoresis (2-DE) can be used to study protein expression in defined brain regions, but mainly the proteins which are present in high abundance in glia are readily detected. The current study was undertaken to determine the protein profile in a synaptosomal subcellular fraction isolated from the cerebral cortex of the rat. Both 2-DE and liquid chromatography - tandem mass spectrometry (LC-MS/MS) procedures were used to isolate and identify proteins in the synaptosomal fraction and accordingly >900 proteins were detected using 2-DE; the 167 most intense gel spots were isolated and identified with matrix-assisted laser desorption/ionization - time of flight peptide mass fingerprinting or LC-MS/MS. In addition, over 200 proteins were separated and identified with the LC-MS/MS "shotgun proteomics" technique, some in post-translationally modified form. The following classes of proteins associated with synaptic function were detected: (a) proteins involved in synaptic vesicle trafficking-docking (e.g., SNAP-25, synapsin I and II, synaptotagmin I, II, and V, VAMP-2, syntaxin 1A and 1B, etc.); (b) proteins that function as transporters or receptors (e.g., excitatory amino acid transporters 1 and 2, GABA transporter 1); (c) proteins that are associated with the synaptic plasma membrane (e.g., post-synaptic density-95/synapse-associated protein-90 complex, neuromodulin (GAP-43), voltage-dependent anion-selective channel protein (VDACs), sodium-potassium ATPase subunits, alpha 2 spectrin, septin 7, etc.); and (d) proteins that mediate intracellular signaling cascades that modulate synaptic function (e.g., calmodulin, calcium-calmodulin-dependent protein kinase subunits, etc.). Other identified proteins are associated with mitochondrial or general cytosolic function. Of the two proteins identified as endoplasmic reticular, both interact with the synaptic SNARE complex to regulate vesicle trafficking. Taken together, these results suggest that the integrity of the synaptosomes was maintained during the isolation procedure and that this subcellular fractionation technique enables the enrichment of proteins associated with synaptic function. The results also suggest that this experimental approach can be used to study the differential expression of multiple proteins involved in alterations of synaptic function.
Keywords: Animals; Biological; Cerebral Cortex; Chromatography; Computational Biology; Electrophoresis; Gel; Glycoproteins; Isoelectric Point; Liquid; Male; Mass; Mass Spectrometry; Matrix-Assisted Laser Desorption-Ionization; Models; Post-Translational; Protein Processing; Proteomics; Rats; Spectrometry; Synaptosomes; Trypsin; Two-Dimensional; Wistar

Reconstructing the pathways of a cellular system from genome-scale signals by using matrix and tensor computations - Alter, Orly; Golub, Gene H. (Proceedings of the National Academy of Sciences of the United States of America, 2005)
We describe the use of the matrix eigenvalue decomposition (EVD) and pseudoinverse projection and a tensor higher-order EVD (HOEVD) in reconstructing the pathways that compose a cellular system from genome-scale nondirectional networks of correlations among the genes of the system. The EVD formulates a genes × genes network as a linear superposition of genes × genes decorrelated and decoupled rank-1 subnetworks, which can be associated with functionally independent pathways. The integrative pseudoinverse projection of a network computed from a “data” signal onto a designated “basis” signal approximates the network as a linear superposition of only the subnetworks that are common to both signals and simulates observation of only the pathways that are manifest in both experiments. We define a comparative HOEVD that formulates a series of networks as linear superpositions of decorrelated rank-1 subnetworks and the rank-2 couplings among these subnetworks, which can be associated with independent pathways and the transitions among them common to all networks in the series or exclusive to a subset of the networks. Boolean functions of the discretized subnetworks and couplings highlight differential, i.e., pathway-dependent, relations among genes. We illustrate the EVD, pseudoinverse projection, and HOEVD of genome-scale networks with analyses of yeast DNA microarray data.
Keywords: DNA microarrays; eigenvalue decomposition; higher-order eigenvalue decomposition; pseudoinverse projection; yeast Saccharomyces cerevisiae cell cycle and mating

Revealing alcohol abuse: to ask or to test? - Alling, C.; Chick, J. D.; Anton, R.; Mayfield, R. D.; Salaspuro, M.; Helander, A.; Harris, R. A. (Alcoholism, Clinical and Experimental Research, 2005)
Keywords: Accidents; Alcoholic Intoxication; alcoholism; Biomarkers; Europe; Genomics; Humans; Mass Screening; Proteomics; Self Disclosure; Sensitivity and Specificity; Traffic; Transferrin; Treatment Outcome

Role of the endogenous opioid system on the neuropsychopharmacological effects of ethanol: new insights about an old question - Sanchis-Segura, Carles; Grisel, Judy E.; Olive, M. Foster; Ghozland, Sandra; Koob, George F.; Roberts, Amanda J.; Cowen, Michael S. (Alcoholism, Clinical and Experimental Research, 2005)
This article presents the proceedings of the symposium "Endogenous Opioids and Voluntary Ethanol Consumption: What Have We Learnt From Knock-out Mice?" presented at the meeting of the International Society for Biomedical Research on Alcoholism held in Heidelberg/Mannheim, Germany, in September/October 2004. The organizers and chairpersons were Michael S. Cowen and Carles Sanchis-Segura. The presentations were as follows: (1) Regulation of the Opioid System by Alcohol: Comparison of Alcohol-Preferring and -Nonpreferring Strains by Michael S. Cowen; (2) Endogenous Opioids and Alcohol: Lessons From Microdialysis and Knock-out Mice by M. Foster Olive; (3) From Neurochemistry to Neuroanatomy: The Hypothalamic Arcuate Nucleus as a Main Site for Ethanol-Opioids Interaction by Carles Sanchis-Segura; (4) Sensitivity to Ethanol Is Modulated by beta-Endorphin in Transgenic Mice by Judy E. Grisel, Amanda J. Roberts, and George F. Koob; and () The mu-Opioid Receptor Modulates Acute Ethanol Sensitivity and Ethanol Withdrawal Severity by Sandra Ghozland.
Keywords: Alcohol Withdrawal Delirium; alcoholism; Animals; Arcuate Nucleus of Hypothalamus; beta-Endorphin; Brain; Ethanol; Humans; Knockout; Mice; Motivation; mu; Opioid; Receptors; Transgenic

Scheduled access to ethanol results in motor impairment and tolerance in female C57BL/6J mice - Cronise, K.; Finn, D. A.; Metten, P.; Crabbe, J. C. (Pharmacology Biochemistry and Behavior, 2005)
We recently reported a method where water-restricted mice were given scheduled access to ethanol followed by access to water. C57BL/6J mice would repeatedly self-administer ethanol in amounts that produced high and stable blood ethanol concentrations (BEC) [Finn DA, Belknap JK, Cronise K, Yoneyama N, Murillo A, Crabbe JC. A procedure to produce high alcohol intake in mice. Psychopharmacol 2005;178:471–480]. The studies reported here demonstrate that behavioral signs of motor impairment result from these high alcohol intakes, and that there was some evidence of tolerance development across repeated sessions. Female C57BL/6J mice were allowed 30 min access to ethanol (5% v/v) followed by 2.5 h access to water either: every 3rd day for 12 days; every 2nd day for 28 days; or every 2nd day for 9 days. On intervening days, mice had 3 h access to water. A control group had daily access to water only. Mice consumed 2–2.5 g/kg ethanol in 30 min, resulting in BECs of 1.4–1.5 mg/ml. Motor impairment was assessed using the accelerating or fixed speed rotarod, balance beam or screen test. In all studies, mice were tested for motor impairment immediately after 30 min access to ethanol or water. In Experiment 1, ethanol-exposed mice had shorter latencies to fall from the fixed speed rotarod and more foot slips on the balance beam than the control group, indicating motor impairment. After drinking ethanol, mice also fell from a screen more quickly than during sober pretraining. In Experiment 2, mice tested (without prior training) for motor impairment and tolerance on the fixed speed rotarod at 6.5 and 10 RPM showed repeated motor impairment in the ethanol group, but did not develop tolerance. In Experiment 3, mice were first given rotarod training at 10 RPM. Following each fluid access period, performance was impaired in mice self-administering ethanol at 10, but not 15 RPM, when compared to control mice. There was no evidence of tolerance across days. However, on the last day, all mice were tested at both RPM following an i.p. injection of 2 g/kg ethanol. Ethanol-experienced mice were less impaired at both RPM than the ethanol-naïve mice, indicating tolerance development according to this between-groups index. These results suggest that C57BL/6J mice will repeatedly consume alcohol in amounts that produce motor impairment under these scheduled fluid access conditions, and that a modest degree of tolerance can be detected using appropriate tests.
Keywords: alcohol; Consumption; Intoxication; Motor incoordination; Mouse; Rotarod; self-administration; Tolerance

Stress enhancement of craving during sobriety: a risk for relapse - Breese, George R.; Chu, Kathleen; Dayas, Christopher V.; Funk, Douglas; Knapp, Darin J.; Koob, George F.; Lê, Dzung Anh; O'Dell, Laura E.; Overstreet, David H.; Roberts, Amanda J.; Sinha, Rajita; Valdez, Glenn R.; et al. (Alcoholism, Clinical and Experimental Research, 2005)
This report of the proceedings of a symposium presented at the 2004 Research Society on Alcoholism Meeting provides evidence linking stress during sobriety to craving that increases the risk for relapse. The initial presentation by Rajita Sinha summarized clinical evidence for the hypothesis that there is an increased sensitivity to stress-induced craving in alcoholics. During early abstinence, alcoholics who were confronted with stressful circumstances showed increased susceptibility for relapse. George Breese presented data demonstrating that stress could substitute for repeated withdrawals from chronic ethanol to induce anxiety-like behavior. This persistent adaptive change induced by multiple withdrawals allowed stress to induce an anxiety-like response that was absent in animals that were not previously exposed to chronic ethanol. Subsequently, Amanda Roberts reviewed evidence that increased drinking induced by stress was dependent on corticotropin-releasing factor (CRF). In addition, rats that were stressed during protracted abstinence exhibited anxiety-like behavior that was also dependent on CRF. Christopher Dayas indicated that stress increases the reinstatement of an alcohol-related cue. Moreover, this effect was enhanced by previous alcohol dependence. These interactive effects between stress and alcohol-related environmental stimuli depended on concurrent activation of endogenous opioid and CRF systems. A.D. Lê covered information that indicated that stress facilitated reinstatement to alcohol responding and summarized the influence of multiple deprivations on this interaction. David Overstreet provided evidence that restraint stress during repeated alcohol deprivations increases voluntary drinking in alcohol-preferring (P) rats that results in withdrawal-induced anxiety that is not observed in the absence of stress. Testing of drugs on the stress-induced voluntary drinking implicated serotonin and CRF involvement in the sensitized response. Collectively, the presentations provided convincing support for an involvement of stress in the cause of relapse and continuing alcohol abuse and suggested novel pharmacological approaches for treating relapse induced by stress.
Keywords: Addictive; Animals; Behavior; Humans; Physiological; Risk Factors; Secondary Prevention; Stress; Temperance

Synergistic effects of the peptide fragment D-NAPVSIPQ on ethanol inhibition of synaptic plasticity and NMDA receptors in rat hippocampus - Zhang, T. A.; Hendricson, A. W.; Wilkemeyer, M. F.; Lippmann, M. J.; Charness, M. E.; Morrisett, R. A. (Neuroscience, 2005)
The L1 cell adhesion molecule has been implicated in ethanol teratogenesis as well as NMDAR-dependent long-term potentiation (LTP) of synaptic transmission, a process thought to be critical for neural development. Ethanol inhibits LTP at least in part by interacting with NMDA receptors. Ethanol also inhibits L1-mediated cell adhesion in a manner that is prevented by an octapeptide, D-NAPVSIPQ (D-NAP), as well as long chain alcohols such as 1-octanol. Here we analyzed the effects of D-NAP and 1-octanol on ethanol modulation of LTP induced by theta burst stimulation in two subfields of the rat hippocampus, the dentate gyrus and area CA1. When theta burst stimulation was delivered in ethanol (50 mM), LTP was inhibited by about 50%. Surprisingly, when D-NAP (10(-7) M) and ethanol were co-applied or applied sequentially, LTP was completely absent. The effects of D-NAP were persistent, since delivery of a second theta burst stimulation following washout of D-NAP and ethanol elicited minimal plasticity. Application of D-NAP alone had no effect on LTP induction or expression. The synergistic effect of D-NAP on ethanol inhibition of LTP was concentration-dependent since D-NAP (10(-10) M) had an intermediate effect, while D-NAP (10(-13) M) had no effect on ethanol suppression of LTP. These observations were also replicated with a different ethanol antagonist, 1-octanol, in area CA1. To address the mechanisms underlying this long-lasting suppression of LTP, the sensitivity of pharmacologically isolated NMDAR extracellular field potentials to combinations of D-NAP and ethanol was determined. D-NAP (10(-7)M) alone had no effect on NMDA extracellular field potentials; however, the peptide significantly increased the inhibitory action of ethanol on NMDA extracellular field potential. The findings suggest that D-NAP and 1-octanol selectively interact with NMDA receptors in an ethanol-dependent manner, further implicating the L1 cell adhesion molecule in alcohol-related brain disorders.
Keywords: Animals; Cell Adhesion; Electric Stimulation; Ethanol; Female; Hippocampus; Long-Term Potentiation; Male; N-Methyl-D-Aspartate; Oligopeptides; Rats; Receptors; Sprague-Dawley

The syntaxin binding protein 1 gene (Stxbp1) is a candidate for an ethanol preference drinking locus on mouse chromosome 2 - Fehr, Christoph; Shirley, Renee L.; Crabbe, John C.; Belknap, John K.; Buck, Kari J.; Phillips, Tamara J. (Alcoholism, Clinical and Experimental Research, 2005)
{BACKGROUND: We previously mapped a quantitative trait locus (QTL) for ethanol preference drinking to mouse chromosome 2 (mapped with high confidence
Keywords: Alcohol Drinking; Animals; Avoidance Learning; Central Nervous System Depressants; Chromosomes; Ethanol; Female; Gene Expression; Genetic; Genotype; Inbred Strains; Male; Messenger; Mice; Munc18 Proteins; Nerve Tissue Proteins; Polymorphism; RNA; Substance Withdrawal Syndrome; Taste; Vesicular Transport Proteins

The tipsy terminal: Presynaptic effects of ethanol - Siggins, George Robert; Roberto, Marisa; Nie, Zhiguo (Pharmacology & Therapeutics, 2005)
Considerable evidence suggests that the synapse is the most sensitive CNS element for ethanol effects. Although most alcohol research has focussed on the postsynaptic sites of ethanol action, especially regarding interactions with the glutamatergic and GABAergic receptors, few such studies have directly addressed the possible presynaptic loci of ethanol action, and even fewer describe effects on synaptic terminals. Nonetheless, there is burgeoning evidence that presynaptic terminals play a major role in ethanol effects. The methods used to verify such ethanol actions range from electrophysiological analysis of paired-pulse facilitation (PPF) and spontaneous and miniature synaptic potentials to direct recording of ion channel activity and transmitter/messenger release from acutely isolated synaptic terminals, and microscopic observation of vesicular release, with a focus predominantly on GABAergic, glutamatergic, and peptidergic synapses. The combined data suggest that acute ethanol administration can both increase and decrease the release of these transmitters from synaptic terminals, and more recent results suggest that prolonged or chronic ethanol treatment (CET) can also alter the function of presynaptic terminals. These new findings suggest that future analyses of synaptic effects of ethanol should attempt to ascertain the role of presynaptic terminals and their involvement in alcohol's behavioral actions. Other future directions should include an assessment of ethanol's effects on presynaptic signal transduction linkages and on the molecular machinery of transmitter release and exocytosis in general. Such studies could lead to the formulation of new treatment strategies for alcohol intoxication, alcohol abuse, and alcoholism.
Keywords: alcohol; GABA; glutamate; Intoxication; Peptides; Synapses

Treatment with and withdrawal from finasteride alter ethanol intake patterns in male C57BL/6J mice: potential role of endogenous neurosteroids? - Ford, Matthew M.; Nickel, Jeffrey D.; Finn, Deborah A. (Alcohol (Fayetteville, N.Y.), 2005)
Exogenous administration of the gamma-aminobutyric acid (GABA)-ergic neurosteroid allopregnanolone (ALLO) can increase ethanol intake in rats and mice. To determine the contribution of endogenous neurosteroids (i.e., ALLO and related pregnane steroids) in the regulation of established ethanol consumption patterns in male C57BL/6J (B6) mice, the 5alpha-reductase (5alpha-R) enzyme inhibitor, finasteride (FIN), was chronically administered and then subsequently withdrawn. Mice were provided daily 2-h limited access to a 10% vol/vol ethanol solution (10E) and water in lickometer chambers during the dark phase. Following the establishment of stable 10E intake patterns, mice were injected intraperitoneally with either vehicle (20% wt/vol 2-hydroxypropyl-beta-cyclodextrin; n=8) or FIN (50 mg/kg; n=16) for 7 days. Effects of withdrawal from FIN treatment were subsequently assessed for an additional 7 days. Ethanol intakes were significantly decreased with acute FIN treatment (days 1-3) and during early withdrawal (days 1-3). Acute FIN treatment was also associated with an extended latency to first bout, reduced first bout size, and greatly attenuated sipper contact count during the initial 20-min interval of 10E access. These findings collectively indicated that acute FIN treatment markedly attenuated the initiation of 10E consumption during the limited access sessions. The influence of FIN on 10E intake patterns was largely dissipated with chronic treatment, suggesting that compensatory changes in neurosteroid modulation of inhibitory tone may have occurred. Thus, acute FIN treatment modulated ethanol intake patterns in a manner opposite to that previously demonstrated for a physiologically relevant, exogenous ALLO dose, consistent with the ability of a alpha-R inhibitor to block ALLO biosynthesis. Manipulation of endogenous neurosteroid activity via biosynthetic enzyme inhibition or antagonism of steroid binding to the GABA type A receptor may prove to be a beneficial pharmacotherapeutic strategy in the intervention of alcohol abuse and alcoholism.
Keywords: Alcohol Drinking; Animals; Drinking; Enzyme Inhibitors; Ethanol; Finasteride; GABA-A; Inbred C57BL; Male; Mice; Pregnanolone; Receptors; Self Administration; Steroids

Urocortin 1 expression in five pairs of rat lines selectively bred for differences in alcohol drinking - Turek, V. F.; Tsivkovskaia, N. O.; Hyytia, P.; Harding, S.; Lê, A. D.; Ryabinin, A. E. (Psychopharmacology, 2005)
RATIONALE: There is accumulating evidence that the neuropeptide urocortin 1 (Ucn1) is involved in alcohol consumption. Thus far, however, most studies have been performed in mice. OBJECTIVES: The purpose of the present study was to characterize Ucn1 expression in rats selectively bred for either high or low alcohol intake. METHODS: Brains from naive male rats of five pairs of independently selected lines (iP/iNP, AA/ANA, HARF/LARF, HAD1/LAD1, and HAD2/LAD2) were analyzed by immunohistochemistry. RESULTS: Significant differences were found between iP/iNP, HARF/LARF, and HAD2/LAD2 in number of Ucn1-containing cells in the Edinger-Westphal (EW) nucleus (the main source of Ucn1 in the brain), whereas no significant differences were found between HAD1/LAD1 and AA/ANA. Similarly, significant differences in the optical density of Ucn1 immunoreactivity in EW were found between iP/iNP, HARF/LARF, and HAD2/LAD2, whereas no differences on this measure were found between HAD1/LAD1 and AA/ANA. In the lateral septum (LS, the main projection area of Ucn1-containing neurons in the rat), significant differences were found only between AA/ANA and HAD2/LAD2; however, a meta-analysis indicated that across all five lines, preferring animals had a significantly greater number of Ucn1-positive fibers than nonpreferring animals. CONCLUSIONS: These results provide evidence that, in rats, Ucn1 may be involved in regulation of alcohol intake, and that this regulation may occur through the Ucn1 projections to LS.
Keywords: Alcohol Drinking; Animals; Brain; Brain Mapping; Corticotropin-Releasing Hormone; Gene Expression; Genetic; Inbred Strains; Nerve Net; Phenotype; Rats; Selection; Septum Pellucidum; Urocortins

Acute and Chronic Ethanol Alter Glutamatergic Transmission in Rat Central Amygdala: an In Vitro and In Vivo Analysis - Roberto, Marisa; Schweitzer, Paul; Madamba, Samuel G.; Stouffer, David G.; Parsons, Loren H.; Siggins, George R. (Journal of Neuroscience, 2004)
The modulation of glutamatergic transmission by ethanol may contribute to ethanol intoxication, reinforcement, tolerance, and dependence. Therefore, we used in vitro electrophysiological and in vivo microdialysis techniques to investigate the effects of acute and chronic ethanol on glutamatergic transmission in the central nucleus of amygdala (CeA). Superfusion of 5-66 mm ethanol decreased compound glutamatergic EPSPs and EPSCs in CeA neurons, with half-maximal inhibition elicited by 14 mm ethanol. Ethanol (44 mm) decreased both non-NMDAR- and NMDAR-mediated EPSPs and EPSCs by 21%. Both the ethanol- and ifenprodil-induced depression of NMDAR-mediated EPSPs and EPSCs was enhanced in rats that received chronic ethanol treatment (CET). Ifenprodil also occluded the ethanol effect, suggesting that NR2B subunit-containing receptors may be involved. With local applications of NMDA, acute ethanol elicited a greater inhibition of NMDA currents in slices taken from CET (47%) compared with naive (30%) animals, suggesting that CET sensitizes NMDA receptors to ethanol. Acute ethanol also reduced paired pulse facilitation of EPSPs and EPSCs only in CET animals, suggesting acute ethanol-induced increase of glutamate release. This finding was supported by in vivo experiments showing that infusion of ethanol (0.1-1 m) via reverse microdialysis significantly increased glutamate release into the CeA dialysate but only after CET. Moreover, baseline CeA glutamate content was significantly higher in CET compared with naive animals. These combined findings suggest that CET and withdrawal lead to neuroadaptations of glutamatergic transmission at both presynaptic and postsynaptic sites in CeA, and glutamatergic synapses in CeA may play an important role in ethanol dependence.
Keywords: alcohol; chronic alcohol treatment; Electrophysiology; ethanol dependence; Microdialysis; NMDA; paired pulse facilitation

Alcohol and inhibitory receptors: unexpected specificity from a nonspecific drug - Harris, R. A.; Mihic, S. J. (Proceedings of the National Academy of Sciences of the United States of America, 2004)
Keywords: Animals; Drug Resistance; Ethanol; GABA-A; Humans; Knockout; Mice; Protein Subunits; Receptors; Species Specificity

Altered representation of the spatial code for odors after olfactory classical conditioning; memory trace formation by synaptic recruitment - Yu, Dinghui; Ponomarev, Artem; Davis, Ronald L. (Neuron, 2004)
In the olfactory bulb of vertebrates or the homologous antennal lobe of insects, odor quality is represented by stereotyped patterns of neuronal activity that are reproducible within and between individuals. Using optical imaging to monitor synaptic activity in the Drosophila antennal lobe, we show here that classical conditioning rapidly alters the neural code representing the learned odor by recruiting new synapses into that code. Pairing of an odor-conditioned stimulus with an electric shock-unconditioned stimulus causes new projection neuron synapses to respond to the odor along with those normally activated prior to conditioning. Different odors recruit different groups of projection neurons into the spatial code. The change in odor representation after conditioning appears to be intrinsic to projection neurons. The rapid recruitment by conditioning of new synapses into the representation of sensory information may be a general mechanism underlying many forms of short-term memory.
Keywords: Animals; Classical; Conditioning; Drosophila; Drosophila Proteins; Electroshock; Genetically Modified; Memory; Neurophysiological; Odorants; olfactory bulb; Recruitment; Smell; Synapses

Are sobriety and consciousness determined by water in protein cavities? - Trudell, James R.; Harris, R. Adron (Alcoholism, Clinical and Experimental Research, 2004)
Keywords: Abdominal Cavity; Animals; Binding Sites; Consciousness; Humans; Odorant; Proteins; Receptors; Temperance; Water

Blockade of the leptin-sensitive pathway markedly reduces alcohol consumption in mice - Blednov, Yuri A.; Walker, Danielle; Harris, R. Adron (Alcoholism, Clinical and Experimental Research, 2004)
BACKGROUND: The neuropeptide leptin links adipose stores with hypothalamic centers and serves as an endocrine signal involved in the regulation of appetite (and possibly in the endorphinergic modulation of the drug reward system). Increased plasma leptin has been observed at the onset of alcohol withdrawal in humans, and ethanol consumption after withdrawal was increased by injection of leptin in mice. We addressed the role of leptin in alcohol-related behaviors by studying ethanol consumption in two strains of spontaneously mutant mice that lack leptin (ob/ob) or the leptin receptor (db/db). METHODS: Two strains of mutant leptin-deficient (ob/ob) or leptin-resistant (db/db) mice were tested in a two-bottle-choice paradigm and were compared with wild-type (C57BL/6 inbred strain) mice. The effects of leptin injection on voluntary ethanol intake have been investigated in ob/ob and C57BL/6 mice. RESULTS: Males and females of both mutant strains showed a significantly lower preference for alcohol in a two-bottle-choice paradigm compared with wild-type mice. Male ob/ob mice demonstrated slightly higher avoidance of bitter taste, and females of the both mutant strains showed a reduced preference for saccharin solutions. Administration of leptin (1 mg/kg intraperitoneally, daily for 8 days) altered body weight but failed to increase the preference for ethanol in ob/ob mice; i.e., we could not correct the effects of leptin deficiency on alcohol consumption by the injection of leptin. Also, there were no differences between the effects of leptin (1 mg/kg intraperitoneally, daily for 8 days) and saline injections on alcohol consumption in C57BL/6 mice. CONCLUSIONS: These data show that blockade of the leptin pathway markedly decreases the preference for alcohol intake, but this decrease may be the result of compensatory or developmental changes in other systems rather than a more direct effect of leptin on alcohol consumption.
Keywords: Alcohol Drinking; Animals; Dose-Response Relationship; Drug; Female; Inbred C57BL; Knockout; Leptin; Male; Mice; Obese; Species Specificity

Comparison of intracranial self-administration of ethanol within the posterior ventral tegmental area between alcohol-preferring and Wistar rats - Rodd, Zachary A.; Bell, Richard L.; Melendez, Roberto I.; Kuc, Kelly A.; Lumeng, Lawrence; Li, Ting-Kai; Murphy, James M.; McBride, William J. (Alcoholism, Clinical and Experimental Research, 2004)
BACKGROUND: A previous study indicated that selectively bred alcohol-preferring (P) rats self-administered ethanol (EtOH) directly into the ventral tegmental area (VTA), whereas the alcohol-nonpreferring line did not. Wistar rats will also self-administer EtOH directly into the posterior VTA. Because Wistar rats also have a low preference for EtOH solutions but self-inject EtOH into the VTA, this study was undertaken to test the hypothesis that there is an association between EtOH preference and sensitivity of the VTA to the reinforcing effects of EtOH. METHODS: Adult P and Wistar rats were assigned to groups that received one of the following concentrations of EtOH: 0, 50, 75, 100, 150, or 200 mg/100 ml. Rats were connected to the microinjection system, placed into two-lever (active and inactive) experimental chambers, and given EtOH for the first four sessions (acquisition), artificial cerebrospinal fluid for sessions 5 and 6 (extinction), and EtOH again in session 7 (reinstatement). Responding on the active lever produced a 100-nl injection of the infusate. RESULTS: P rats self-infused 75 to 200 mg/100 ml EtOH and demonstrated lever discrimination, whereas Wistar rats reliably self-infused only 150 and 200 mg/100 ml EtOH. Both P and Wistar rats reduced responding on the active lever when artificial cerebrospinal fluid (aCSF) was substituted for EtOH and reinstated responding in session 7 when EtOH was restored, although P rats demonstrated a very robust enhancement of responding for 100 and 150 mg/100 ml EtOH, and this was not found for Wistar rats. CONCLUSIONS: These results suggest that, compared with Wistar rats, the posterior VTA of P rats was more sensitive to the reinforcing effects of EtOH. Furthermore, the reinstatement data suggest that the posterior VTA of P rats underwent neuronal alterations as a result of prior EtOH exposure and extinction that changed the reinforcing effects of EtOH within this region.
Keywords: Alcohol Drinking; Animals; Dose-Response Relationship; Drug; Ethanol; Female; Injections; Intraventricular; Rats; Self Administration; Ventral tegmental area; Wistar

Convergent analysis of cDNA and short oligomer microarrays, mouse null mutants and bioinformatics resources to study complex traits - Ponomarev, I.; Schafer, G. L.; Blednov, Y. A.; Williams, R. W.; Iyer, V. R.; Harris, R. A. (Genes, Brain, and Behavior, 2004)
Gene expression data sets have recently been exploited to study genetic factors that modulate complex traits. However, it has been challenging to establish a direct link between variation in patterns of gene expression and variation in higher order traits such as neuropharmacological responses and patterns of behavior. Here we illustrate an approach that combines gene expression data with new bioinformatics resources to discover genes that potentially modulate behavior. We have exploited three complementary genetic models to obtain convergent evidence that differential expression of a subset of genes and molecular pathways influences ethanol-induced conditioned taste aversion (CTA). As a first step, cDNA microarrays were used to compare gene expression profiles of two null mutant mouse lines with difference in ethanol-induced aversion. Mice lacking a functional copy of G protein-gated potassium channel subunit 2 (Girk2) show a decrease in the aversive effects of ethanol, whereas preproenkephalin (Penk) null mutant mice show the opposite response. We hypothesize that these behavioral differences are generated in part by alterations in expression downstream of the null alleles. We then exploited the WebQTL databases to examine the genetic covariance between mRNA expression levels and measurements of ethanol-induced CTA in BXD recombinant inbred (RI) strains. Finally, we identified a subset of genes and functional groups associated with ethanol-induced CTA in both null mutant lines and BXD RI strains. Collectively, these approaches highlight the phosphatidylinositol signaling pathway and identify several genes including protein kinase C beta isoform and preproenkephalin in regulation of ethanol- induced conditioned taste aversion. Our results point to the increasing potential of the convergent approach and biological databases to investigate genetic mechanisms of complex traits.
Keywords: Animals; Association Learning; Avoidance Learning; Complementary; Computational Biology; Databases; DNA; Enkephalins; Ethanol; Female; G Protein-Coupled Inwardly-Rectifying Potassium Channels; Gene Expression Profiling; Genetic; Inbred C57BL; Inwardly Rectifying; Knockout; Male; Messenger; Mice; Models; Oligonucleotide Array Sequence Analysis; Phenotype; Potassium Channels; Protein Precursors; RNA; Taste

Deletion of the fyn-kinase gene alters sensitivity to GABAergic drugs: dependence on beta2/beta3 GABAA receptor subunits - Boehm, Stephen L.; Peden, Laura; Harris, R. Adron; Blednov, Yuri A. (The Journal of Pharmacology and Experimental Therapeutics, 2004)
Tyrosine phosphorylation can modulate GABA(A) receptor function, and deletion of the fyn-kinase gene alters GABAergic function in olfactory bulb neurons, as reported by Kitazawa, Yagi, Miyakawa, Niki, and Kawai (J Neurophysiol 1998;79:137-142). Our goal was to determine whether fyn gene deletion altered behavioral and functional actions of compounds that act on GABA(A) receptors. Such evidence might suggest a role for fyn-kinase in modulating GABA(A) receptor function, possibly via direct interactions between the kinase and receptor. Using the loss of righting reflex test, we found that null mutants were less sensitive to the hypnotic effects of THIP (4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol), a GABA(A) receptor agonist. Subunit specificity was suggested by the observation that null mutants were also less sensitive to the hypnotic effects of etomidate, a GABAergic compound that is selective for receptors possessing beta2 and/or beta3 receptor subunits. The genotypes did not differ in sensitivity to zolpidem, an alpha1-selective GABAergic drug. GABA(A) receptor functional assays ((36)Cl(-) influx) supported our behavioral results; the actions of the GABA(A) agonists, THIP and muscimol, were reduced in the cerebellar membranes of fyn-null mutant mice. Importantly, similar results were seen with etomidate. Binding of [(3)H]flunitrazepam supported the idea that this is due to a decrease in functional GABA(A) receptor density. These data suggest that fyn-kinase may alter the function of GABA(A) receptors, perhaps via actions on beta2 and/or beta3 receptor subunits.
Keywords: Animals; Binding Sites; Flunitrazepam; GABA Agonists; GABA Modulators; GABA-A; gamma-Aminobutyric Acid; Gene Deletion; Isoxazoles; Mice; Protein Subunits; Proto-Oncogene Proteins; Proto-Oncogene Proteins c-fyn; Receptors; Reflex; Tritium

Dopamine Transporter Network and Pathways - Maiya, Rajani; Mayfield, R. Dayne (Human Brain Proteome, 2004)
This chapter explains the dopamine transporter network and pathways. The family of Na+ and Cl- dependent transporters that includes the dopamine (DA), and norepinephrine (NE) transporters (DAT and NET, respectively), functions to clear released neurotransmitters from the synaptic cleft. DAT regulates the spatial and temporal aspects of dopaminergic synaptic transmission and is an integral part of the mesostriatal DA system. DAT is also the site of action for various psychostimulants, such as cocaine and amphetamine. The chapter describes the structure and function of DAT. DAT is expressed in cell bodies, dendrites, and axonal membranes of dopaminergic neurons. DAT is localized to the plasma membranes, and smooth endoplasmic reticulum of dendrites and dendritic spines in the substantia nigra. DAT undergoes regulated trafficking both in vitro and in vivo, and this may be important for the functional and pharmacological sensitivity of the transporter. The mass spectrometry (MS) approach helps to identify a network of proteins that exist in a complex with DAT. The MS approaches used are MALDI (matrix-assisted laser desorption ionization) and ESI (electrospray ionization) mass spectrometry.

Effects of concurrent access to a single concentration or multiple concentrations of ethanol on ethanol intake by periadolescent high-alcohol-drinking rats - Bell, Richard L.; Rodd, Zachary A.; Hsu, Cathleen C.; Lumeng, Lawrence; Li, Ting-Kai; Murphy, James M.; McBride, William J. (Alcohol (Fayetteville, N.Y.), 2004)
The objectives of the current study were to assess the effects of access to different concentrations of ethanol and sex of the animal on ethanol consumption of high-alcohol-drinking (HAD-1 and HAD-2) rats during adolescence [postnatal days (PNDs) 30 through 60]. At the beginning of adolescence (PND 30), the rats were given concurrent access to either a single concentration [15% volume/volume (vol./vol.)] or multiple concentrations [10%, 20%, and 30% (vol./vol.)] of ethanol and water. Analyses of ethanol consumption data revealed significant (P < .025) main effects of line, ethanol condition, and week, and a significant line by sex by ethanol condition by week interaction. For the first week, both male and female HAD-1 and HAD-2 rats consumed more ethanol under the multiple ethanol concentration condition than under the single ethanol concentration condition. However, across the second through fourth weeks, this pattern was seen primarily in male and female HAD-1 rats and to a lesser degree in female HAD-2 rats. In general, female rats consumed more fluids than consumed by male rats, and male rats displayed a higher preference for ethanol over water ratio than observed for their female counterparts. In addition, in comparison with HAD-2 rats, HAD-1 rats drank more ethanol and displayed a higher preference for ethanol ratio. Overall, the current study results indicate that, compared with access to a single concentration (which is used in most studies), concurrent access to multiple concentrations of ethanol produced significantly higher ethanol intakes in periadolescent HAD rats, supporting the suggestion that this ethanol drinking condition would have a greater impact on neuronal development. In addition, although the replicate lines were selectively bred by using the same criteria and foundation stock, the higher ethanol intakes of the HAD-1 line, compared with intakes for the HAD-2 line, seen in the current study support the suggestion that there are some differences in their genetic make-up, affecting ethanol intake, which are expressed during periadolescence.
Keywords: Aging; Alcohol Drinking; Animal; Animals; Behavior; Body Weight; Central Nervous System Depressants; Drinking; Ethanol; Female; Male; Neurons; Rats; Sex Characteristics

Effects of long-term episodic access to ethanol on the expression of an alcohol deprivation effect in low alcohol-consuming rats - Bell, Richard L.; Rodd, Zachary A.; Boutwell, Caron L.; Hsu, Cathleen C.; Lumeng, Lawrence; Murphy, James M.; Li, Ting-Kai; McBride, William J. (Alcoholism, Clinical and Experimental Research, 2004)
BACKGROUND: The alcohol-preferring (P) and -nonpreferring (NP) and high alcohol-drinking (HAD) and low alcohol-drinking (LAD) rats have been selectively bred for divergent preference for ethanol over water. In addition, both P and HAD rats display an alcohol deprivation effect (ADE). This study was undertaken to test whether the NP, LAD-1, and LAD-2 lines of rats could display an ADE as well. METHOD: Adult female NP, LAD-1, and LAD-2 rats were given concurrent access to multiple concentrations of ethanol [5, 10, 15% (v/v)] and water in an ADE paradigm involving an initial 6 weeks of 24-hr access to ethanol, followed by four cycles of 2 weeks of deprivation from and 2 weeks of re-exposure to ethanol (5, 10, and 15%). A control group had continuous access to the ethanol concentrations (5, 10, and 15%) and water through the end of the fourth re-exposure period. RESULTS: For NP rats, a preference for the highest ethanol concentration (15%) was evident by the end of the fifth week of access (approximately 60% of total ethanol fluid intake). Contrarily, LAD rats did not display a marked preference for any one concentration of ethanol. All three lines displayed an ADE after repeated cycles of re-exposure to ethanol, with the general ranking of intake being LAD-1 > NP > LAD-2 (e.g., for the first day of reinstatement of the third re-exposure cycle, intakes were 6.5, 2.9, and 2.4 g/kg/day compared with baseline values of 3.1, 2.0, and 1.3 g/kg/day for each line, respectively). By the 13th week, rats from all three lines, with a ranking of LAD-1 > NP > LAD-2, were drinking more ethanol (3.3, 2.2, and 2.0 g/kg/day, respectively) compared with their consumption during the first week of access (approximately 1.1 g/kg/day for all three lines). CONCLUSION: These data indicate that access to multiple concentrations of ethanol and exposure to multiple deprivation cycles can partially overcome a genetic predisposition of NP, LAD-1, and LAD-2 rats for low alcohol consumption. In addition, the findings suggest that genetic control of low alcohol consumption in rats is not associated with the inability to display an ADE.
Keywords: Alcohol Drinking; Animals; Dose-Response Relationship; Drug; Ethanol; Female; Rats; Species Specificity; time; Time Factors

Ethanol augments GABAergic transmission in the central amygdala via CRF1 receptors - Nie, Zhiguo; Schweitzer, Paul; Roberts, Amanda J.; Madamba, Samuel G.; Moore, Scott D.; Siggins, George Robert (Science (New York, N.Y.), 2004)
The central amygdala (CeA) plays a role in the relationship among stress, corticotropin-releasing factor (CRF), and alcohol abuse. In whole-cell recordings, both CRF and ethanol enhanced gamma-aminobutyric acid-mediated (GABAergic) neurotransmission in CeA neurons from wild-type and CRF2 receptor knockout mice, but not CRF1 receptor knockout mice. CRF1 (but not CRF2) receptor antagonists blocked both CRF and ethanol effects in wild-type mice. These data indicate that CRF1 receptors mediate ethanol enhancement of GABAergic synaptic transmission in the CeA, and they suggest a cellular mechanism underlying involvement of CRF in ethanol's behavioral and motivational effects.
Keywords: Alcohol Drinking; Amygdala; Animals; Corticotropin-Releasing Hormone; Dose-Response Relationship; Drug; Ethanol; Evoked Potentials; GABA-A; gamma-Aminobutyric Acid; Inbred C57BL; Knockout; Mice; Neurons; Patch-Clamp Techniques; Psychological; Receptors; Stress; Synaptic Transmission

Ethanol effects on cell signaling mechanisms - Morrow, A. Leslie; Ferrani-Kile, Karima; Davis, Margaret I.; Shumilla, Jennifer A.; Kumar, Sandeep; Maldve, Regina; Pandey, Subhash C. (Alcoholism, Clinical and Experimental Research, 2004)
Keywords: Animals; Ethanol; Humans; MAP Kinase Signaling System; Protein Kinase C; Signal Transduction

Ethanol selectively inhibits enhanced vesicular release at excitatory synapses: real-time visualization in intact hippocampal slices - Maldve, Regina E.; Chen, Xiaochun; Zhang, Tao A.; Morrisett, Richard A. (Alcoholism, Clinical and Experimental Research, 2004)
BACKGROUND: Conflicting information exists concerning the actions of ethanol on vesicular release at excitatory synapses. Because long-term alterations in synaptic transmission are thought to underlie neuroadaptive responses to ethanol, we have directly measured the actions of ethanol on release dynamics at an intact central synapse. METHODS: Here we investigated the effects of ethanol on release dynamics in hippocampal slices using confocal microscopy with the lipophilic dye, FM1-43, complemented by a patch clamp analysis of AMPA miniature excitatory postsynaptic currents (mEPSCs). After a pretreatment/loading paradigm with sulforhodamine (S-Rhd) and FM1-43, stable, dense punctate FM1-43 staining in the CA1 stratum radiatum was evident. RESULTS: FM1-43 fluorescence destaining was dose-dependently induced by perfusion with elevated K+ (20-60 mM). Cadmium inhibited K+-induced destaining, whereas nifedipine had no significant effect. Ethanol (25-75 mM) inhibited K+-induced destaining with high efficacy and had no effect on basal destaining. Both omega-Conotoxin GVIA and omega-Agatoxin IVA inhibited K+-induced destaining with high efficacy. The combination of omega-Conotoxin GVIA and omega-Agatoxin IVA occluded the inhibitory effect of ethanol, indicating that ethanol inhibition of release was dependent on inhibition of N/P/Q-voltage-gated calcium channels (VGCCs). Patch clamp studies of AMPA mEPSCs revealed similar findings in that vesicular release was enhanced with K+ depolarization in an ethanol-sensitive manner. CONCLUSIONS: These findings indicate that the FM1-43/S-Rhd method is a stable and powerful approach for direct real-time measurement of vesicular release kinetics in intact brain slice preparations and that ethanol inhibits vesicular release induced by depolarization via inhibition of N/P/Q-VGCCs.
Keywords: Animals; Ethanol; Excitatory Postsynaptic Potentials; Female; Hippocampus; In Vitro Techniques; Male; Patch-Clamp Techniques; Rats; Sprague-Dawley; Synapses; Synaptic Vesicles; Time Factors

Ethanol-induced Fos immunoreactivity in the extended amygdala and hypothalamus of the rat brain: focus on cholinergic interneurons of the nucleus accumbens - Herring, Bruce E.; Mayfield, R. Dayne; Camp, Marguerite C.; Alcantara, Adriana A. (Alcoholism, Clinical and Experimental Research, 2004)
BACKGROUND: The primary goal of this study was to investigate the effects of varying doses of ethanol on cellular activation, as measured by Fos immunoreactivity, in brain areas that have been implicated in the reinforcing and anxiolytic effects of substance abuse and dependence, namely, the extended amygdala and hypothalamus. Specific regions examined included the central nucleus of the amygdala, bed nucleus of the stria terminalis, substantia innominata, and nucleus accumbens of the extended amygdala, as well as the paraventricular nucleus of the hypothalamus. The cholinergic interneurons of the nucleus accumbens were of particular interest, because these cells have recently been reported to play a pivotal role in substance abuse. METHODS: Adult Sprague-Dawley rats underwent 10 days of handling and 5 days of habituation. Animals then received an injection of saline or 0.5, 1, or 2 g/kg of ethanol. Rats were perfused 2 hr after the injections, and brain sections were processed for single Fos or dual Fos/choline acetyltransferase immunolabeling procedures. The number of Fos-positive neurons was calculated from a 0.45-mm sample area from each of the brain regions examined. RESULTS: A dose of 2 g/kg of ethanol significantly increased the number of Fos-immunoreactive neurons in the central nucleus of the amygdala by 149%, in the shell nucleus accumbens by 80%, and in the paraventricular nucleus of the hypothalamus by 321%. Additionally, 1 g/kg of ethanol significantly increased the percentage of Fos-immunoreactive cholinergic neurons in the nucleus accumbens by 59%. CONCLUSIONS: The findings reported in this study reveal region-specific and dose-dependent changes in Fos immunoreactivity in the extended amygdala and hypothalamus and, more specifically, an increase in neuronal activation of cholinergic cells in the shell nucleus accumbens. These findings contribute to our current knowledge of the brain areas and cellular microcircuits involved in the underlying basis of substance abuse and dependence.
Keywords: Amygdala; Animals; Cholinergic Fibers; Dose-Response Relationship; Drug; Ethanol; hypothalamus; Interneurons; Male; Nucleus Accumbens; Proto-Oncogene Proteins c-fos; Rats; Sprague-Dawley

gamma-Aminobutyric acid A receptor subunit mutant mice: new perspectives on alcohol actions - Boehm, Stephen L.; Ponomarev, Igor; Jennings, Andrew W.; Whiting, Paul J.; Rosahl, Thomas W.; Garrett, Elisabeth M.; Blednov, Yuri A.; Harris, R. Adron (Biochemical Pharmacology, 2004)
gamma-Aminobutyric acid A (GABA(A)) receptors are believed to mediate a number of alcohol's behavioral actions. Because the subunit composition of GABA(A) receptors determines receptor pharmacology, behavioral sensitivity to alcohol (ethanol) may depend on which subunits are present (or absent). A number of knock-out and/or transgenic mouse models have been developed (alpha1, alpha2, alpha5, alpha6, beta2, beta3, gamma2S, gamma2L, delta) and tested for behavioral sensitivity to ethanol. Here we review the current GABA(A) receptor subunit knock-out and transgenic literature for ethanol sensitivity, and integrate these results into those obtained using quantitative trait loci (QTL) analysis and gene expression assays. Converging evidence from these three approaches support the notion that different behavioral actions of ethanol are mediated by specific subunits, and suggest that new drugs that target specific GABA(A) subunits may selectively alter some behavioral actions of ethanol, without altering others. Current data sets provide strongest evidence for a role of alpha1-subunits in ethanol-induced loss of righting reflex, and alpha5-subunits in ethanol-stimulated locomotion. However, three-way validation is hampered by the incomplete behavioral characterization of many of the mutant mice, and additional subunits are likely to be linked to alcohol actions as behavioral testing progresses.
Keywords: Animals; Ethanol; GABA-A; gamma-Aminobutyric Acid; Humans; Knockout; Mice; Motor Activity; Mutation; Protein Subunits; Quantitative Trait Loci; Receptors; Reflex

Gene expression profiling of individual cases reveals consistent transcriptional changes in alcoholic human brain - Liu, Jianwen; Lewohl, Joanne M.; Dodd, Peter R.; Randall, Patrick K.; Harris, R. Adron; Mayfield, R. Dayne (Journal of Neurochemistry, 2004)
Chronic alcohol exposure induces lasting behavioral changes, tolerance, and dependence. This results, at least partially, from neural adaptations at a cellular level. Previous genome-wide gene expression studies using pooled human brain samples showed that alcohol abuse causes widespread changes in the pattern of gene expression in the frontal and motor cortices of human brain. Because these studies used pooled samples, they could not determine variability between different individuals. In the present study, we profiled gene expression levels of 14 postmortem human brains (seven controls and seven alcoholic cases) using cDNA microarrays (46,448 clones per array). Both frontal cortex and motor cortex brain regions were studied. The list of genes differentially expressed confirms and extends previous studies of alcohol responsive genes. Genes identified as differentially expressed in two brain regions fell generally into similar functional groups, including metabolism, immune response, cell survival, cell communication, signal transduction and energy production. Importantly, hierarchical clustering of differentially expressed genes accurately distinguished between control and alcoholic cases, particularly in the frontal cortex.
Keywords: 80 and over; Adult; Aged; alcoholism; Bayes Theorem; Brain; Brain Chemistry; Central Nervous System Depressants; Ethanol; Female; Gene Expression Profiling; Gene Expression Regulation; Genetic; Humans; Male; Messenger; Middle Aged; Myelin Sheath; Nerve Tissue Proteins; Oligonucleotide Array Sequence Analysis; Reverse Transcriptase Polymerase Chain Reaction; RNA; Transcription

In vivo 2D J-resolved magnetic resonance spectroscopy of rat brain with a 3-T clinical human scanner - Adalsteinsson, E.; Hurd, R. E.; Mayer, D.; Sailasuta, N.; Sullivan, E. V.; Pfefferbaum, A. (NeuroImage, 2004)
A clinical 3-T scanner equipped with a custom-made transmit/receive birdcage coil was used to collect 2D J-resolved single-voxel spectroscopy in vivo of rat brain. Four adult Wistar rats were scanned twice each, with a 2-week interval. Voxel size was approximately 5 x 10 x 5 mm(3). Total spectroscopic acquisition time was 14 min for collection of two 4:20 min water-suppressed acquisitions and one 4:20 min acquisition acquired in the absence of water suppression. The unsuppressed water data were used in post-processing to reduce residual water side bands, as well as for metabolite signal normalization to account for variations in coil loading and voxel size. Peak areas were estimated for resonances from N-acetyl aspartate (NAA), creatine, choline, taurine, glutamate, and combined glutamate and glutamine. T(2)-relaxation times were estimated for NAA and creatine. The average deviation from the mean of repeated measures for glutamate, combined glutamate and glutamine, and taurine ranged from 7.6% to 18.3%, while for NAA, creatine, and choline, the deviation was less than 3%. The estimated T(2) values for NAA (mean +/- SD = 330 +/- 57 ms) and creatine (174 +/- 27 ms) were similar to those reported previously for rat brain and for human gray and white matter. These results indicate that reliable, small animal brain MR spectroscopy can be performed on a human clinical 3-T scanner.
Keywords: Anesthesia; Animals; Body Water; Brain Chemistry; Computer-Assisted; Humans; Image Processing; Magnetic Resonance Imaging; Magnetic Resonance Spectroscopy; Rats; Wistar

In vivo structural imaging of the rat brain with a 3-T clinical human scanner - Pfefferbaum, Adolf; Adalsteinsson, Elfar; Sullivan, Edith V. (Journal of Magnetic Resonance Imaging, 2004)
Purpose To examine the feasibility of using product acquisition software on a 3-T human MRI system to acquire high-resolution structural brain images in the rat. Materials and Methods Three sets of dual spin-echo, high-resolution (0.234 × 0.234 mm in-plane, 0.5 mm thick) images covering the entire rat brain were collected and averaged in 66 min. The images had sufficient signal-to-noise ratio (SNR) and resolution for visual identification and manual outlining of exemplary structures, including the lateral ventricles and dorsal and ventral portions of the hippocampus. Further, the data were adequate for unsupervised, automated segmentation, permitting quantification of the dorsolateral ventricles. The images compared favorably with those collected on a 7-T system. Results Interrater reliabilities (intraclass correlations) of manual ventricular scoring were greater than 0.97, and manual vs. automated correlations were 0.97. The variability of lateral ventricular size across animals was substantially higher than that of the hippocampus. Conclusion The large variability of some brain structures that can exist across even a highly selected strain of rats can readily be detected with the use of human 3-T systems for the study of small animals. J. Magn. Reson. Imaging 2004;20:779–785. © 2004 Wiley-Liss, Inc.
Keywords: animal model; Brain; Hippocampus; MRI; rat; segmentation; ventricle

Increased GABA release in the central amygdala of ethanol-dependent rats - Roberto, Marisa; Madamba, Samuel G.; Stouffer, David G.; Parsons, Loren H.; Siggins, George Robert (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2004)
The central nucleus of amygdala (CeA) is important in regulating alcohol consumption and plays a major role in the anxiogenic response to ethanol withdrawal. We showed previously that acute ethanol augments GABA(A) receptor-mediated IPSPs and IPSCs, possibly by a presynaptic mechanism. Here, we have examined the interaction of acute ethanol with the GABAergic system in chronic ethanol-treated (CET) rats using an in vitro CeA slice preparation and in vivo brain microdialysis. We found that in CeA slices from CET rats, the baseline evoked IPSP and IPSC amplitudes were increased, and paired-pulse facilitation ratios were lower than in naive rats, suggesting an increased GABAergic transmission after chronic ethanol treatment. Interestingly, acute ethanol (5-66 mm) significantly enhanced IPSPs and IPSCs equally in CET and naive rats, indicating a lack of tolerance for this effect of acute ethanol. Analysis of miniature IPSC frequency suggests that the increased GABAergic transmission by both acute and chronic ethanol arises from a presynaptic mechanism involving enhanced vesicular release of GABA. These data are supported by microdialysis studies showing that CET rats presented a fourfold increase in baseline GABA dialysate content compared with naive rats. In vivo administration of ethanol (0.1, 0.3, and 1.0 m) produced a dose-dependent increase in GABA release in the CeA dialysate in both CET and naive rats. These combined findings suggest that acute and chronic ethanol increases GABA release in CeA and support previous reports that the behavioral actions of ethanol are mediated, in part, by increased GABAergic transmission in the CeA.
Keywords: alcoholism; Amygdala; Animals; Dose-Response Relationship; Drug; Drug Administration Schedule; Electric Stimulation; Ethanol; gamma-Aminobutyric Acid; Male; Microdialysis; Neurons; Patch-Clamp Techniques; Rats; Sprague-Dawley; Substance-Related Disorders; Synaptic Transmission

Innate differences in neuropeptide Y (NPY) mRNA expression in discrete brain regions between alcohol-preferring (P) and -nonpreferring (NP) rats: a significantly low level of NPY mRNA in dentate gyrus of the hippocampus and absence of NPY mRNA in the medi - Hwang, Bang H.; Suzuki, Ryoji; Lumeng, Lawrence; Li, T.-K.; McBride, William J. (Neuropeptides, 2004)
The neuropeptide Y (NPY) gene in rat chromosome 4 has been shown to play an important role in alcohol-seeking behavior. NPY knockout mice drink more alcohol than wild-type mice, implicating a link between NPY deficiency and high alcohol intake. This is supported by recent studies showing that intracerebroventricular injections of NPY reduce alcohol intake in both alcohol-preferring (P) and high alcohol-drinking rats. However, it is unknown which anatomical NPY systems are involved in alcohol preference. This study was designed to investigate whether there are innate differences in NPY mRNA in cerebral cortical areas, dentate gyrus (DG) of the hippocampus and medial habenular nucleus (MHb) between P and alcohol-nonpreferring (NP) rats, as these discrete brain regions are rich in NPY mRNA. [(33)P]-labeled 28-mer oligodeoxynucleotide probe was applied for the in situ hybridization study to detect the NPY mRNA, measured using quantitative autoradiography. This study revealed an absence of NPY mRNA in the MHb of P rats. We found that NPY mRNA was significantly lower in the DG of P rats than NP rats. This innate difference of NPY mRNA expression in the DG between P and NP rats is region specific. For example, in most of the cerebral cortical areas examined, an innate difference was not seen. Our study suggests that lower NPY gene expression in the DG and MHb of P rats may be factors contributing to some of the phenotypic differences observed between the P and NP lines of rats.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Brain Chemistry; Dentate Gyrus; Gene Expression; Habenula; In Situ Hybridization; Male; Messenger; Neuropeptide Y; Rats; RNA

Lesions of the Edinger-Westphal nucleus in C57BL/6J mice disrupt ethanol-induced hypothermia and ethanol consumption - Bachtell, Ryan K.; Weitemier, Adam Z.; Ryabinin, Andrey E. (The European Journal of Neuroscience, 2004)
The Edinger-Westphal nucleus (EW) is a brain region that has recently been implicated as an important novel neural target for ethanol. Thus, the EW is the only brain region consistently showing elevated c-Fos expression following both voluntary and involuntary ethanol administration. Ethanol-induced c-Fos expression in the EW has been shown to occur in urocortin I-positive neurons. Moreover, previous reports using several genetic models have demonstrated that differences in the EW urocortin I system are correlated with ethanol-mediated behaviours such as ethanol-induced hypothermia and ethanol consumption. The aim of this study was to confirm these relationships using a more direct strategy. Thus, ethanol responses were measured following electrolytic lesions of the EW in male C57BL/6J mice. Both EW-lesioned and sham-operated animals were tested for several ethanol sensitivity measures and ethanol consumption in a two-bottle choice test. The results show that lesions of the EW significantly disrupted ethanol-induced hypothermia, while having no effect on pupillary dilation, locomotor activity or ethanol-induced sedation. In addition, EW-lesioned animals showed significantly lower ethanol preference and total ethanol dose consumed in the two-bottle choice test. EW-lesioned animals also consumed less sucrose than sham-operated animals, but did not have altered preferences for sucrose or quinine in a two-bottle choice test. These data support previously observed genetic correlations between EW urocortin I expression and both ethanol-induced hypothermia and ethanol consumption. Taken together, the findings suggest that the EW may function as a sensor for ethanol, which can influence ethanol consumption and preference.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Body Temperature; Brain Diseases; Cell Count; Central Nervous System Depressants; Corticotropin-Releasing Hormone; Drinking Behavior; Ethanol; Food Preferences; Hypothermia; Immunohistochemistry; Inbred C57BL; Induced; Male; Mice; Motor Activity; Pupil; Quinine; Sucrose; Tegmentum Mesencephali; Urocortins

Mice lacking metabotropic glutamate receptor 4 do not show the motor stimulatory effect of ethanol - Blednov, Yuri A.; Walker, Danielle; Osterndorf-Kahanek, Elizabeth; Harris, R. Adron (Alcohol, 2004)
Group III metabotropic glutamate receptors (mGluRs), specifically receptors 4, 6, 7, and 8 (i.e., mGluR4, mGluR6, mGluR7, mGluR8), play an important role in the generation of locomotion as well as in the behavioral effects of some psychostimulants. Because the arousing or stimulant effects of ethanol seem to be relevant behavioral traits associated with its rewarding properties and genetic susceptibility to alcoholism, we addressed the role of mGluR4 by studying behavioral actions of ethanol in mutant mice lacking mGluR4. Null mutant mice showed higher motor response to novelty than did wild-type mice. Ethanol (1.0–2.5 g/kg) stimulated motor activity of wild-type mice, but not of null mutant mice. There were no significant differences between wild-type and knockout strains in ethanol consumption or preference in two-bottle paradigm, severity of ethanol-induced acute withdrawal, or duration of loss of righting reflex. These results show that mGluR4 may play a role in locomotor activity in general and also display specificity for mediation of the motor stimulant effect of ethanol. Consistent with findings of other studies, these results confirm the lack of correlation between ethanol-induced motor stimulation and consumption of ethanol measured in a self-administration paradigm in mice.
Keywords: Ethanol; Intake; Knockout mice; mGluR4; Motor Activity

Mu opioid receptor: a gateway to drug addiction - Contet, Candice; Kieffer, Brigitte L.; Befort, Katia (Current Opinion in Neurobiology, 2004)
Mu opioid receptors mediate positive reinforcement following direct (morphine) or indirect (alcohol, cannabinoids, nicotine) activation, and our understanding of mu receptor function is central to the development of addiction therapies. Recent data obtained in native neurons confirm that mu receptor signaling and regulation are strongly agonist-dependent. Current functional mapping reveals morphine-activated neurons in the extended amygdala and early genomic approaches have identified novel mu receptor-associated proteins. A classification of about 30 genes either promoting or counteracting the addictive properties of morphine is proposed from the analysis of knockout mice data. The targeting of effectors or regulatory proteins, beyond the mu receptor itself, might provide valuable strategies to treat addictive disorders.
Keywords: Animals; Brain; Gene Expression Regulation; Humans; Morphine; mu; Narcotics; Nerve Tissue Proteins; Neural Pathways; Opioid; Receptors; Signal Transduction; Substance-Related Disorders

Observer-rated ataxia: rating scales for assessment of genetic differences in ethanol-induced intoxication in mice - Metten, Pamela; Best, Karyn L.; Cameron, Andy J.; Saultz, Alisha B.; Zuraw, Jessica M.; Yu, Chia-Hua; Wahlsten, Douglas; Crabbe, John C. (Journal of Applied Physiology (Bethesda, Md.: 1985), 2004)
Identification of genetic and physiological mechanisms underlying a drug's or mutation's effects on motor performance could be aided by the existence of a simple observation-based rating scale of ataxia for mice. Rating scales were developed to assess ataxia after ethanol (2.75, 3.0, and 3.25 g/kg) in nine inbred mouse strains. Each scale independently rates a single behavior. Raters, blinded to dose, scored four behaviors (splay of hind legs, wobbling, nose down, and belly drag) at each of four time points after injection. The severities of hind leg splaying and wobbling were quantifiable, whereas nose down and belly dragging were expressed in all-or-none fashion. Interrater reliabilities were substantial (0.75 \textlessor= r \textlessor= 0.99). Splay scores (rated 0-5) displayed significant effects of strain, dose, and time point. Wobbling (rated 0-4) was dependent on strain and time point. Ethanol affected wobbling (most strains scored >0 at some time), but all doses were equally effective. Incidence of nose down and belly dragging behaviors increased strain dependently after ethanol, but strains did not differentially respond to dose. Ethanol-induced splaying was modestly, and negatively, genetically correlated with wobbling. Nose down and belly dragging tended to be associated with splaying and wobbling at later times. Four distinct ataxia-related behaviors were sensitive to ethanol. Strains differed in ethanol sensitivity for all measures. Modest strain mean correlations among behaviors indicate that these behaviors are probably under control of largely different genes and that ataxia rating scales should rate separate behaviors on discrete scales.
Keywords: Alcoholic Intoxication; Animal; Animals; Behavior; Central Nervous System Depressants; Dose-Response Relationship; Drug; Ethanol; Female; Gait Ataxia; Hindlimb; Inbred BALB C; Inbred C57BL; Locomotion; Male; Mice; Observer Variation; Phenotype; Postural Balance; Posture; Reflex; Species Specificity

Over-expression of the fyn-kinase gene reduces hypnotic sensitivity to ethanol in mice - Boehm II, Stephen L.; Peden, Laura; Jennings, Andrew W.; Kojima, Nobuhiko; Harris, R. Adron; Blednov, Yuri A. (Neuroscience Letters, 2004)
Our previous work indicated a role for fyn-kinase in mediating several ethanol- and GABAA agonist-mediated behaviors. In the present work we investigate behavioral sensitivity to ethanol and several GABAA compounds in mice that over-express fyn-kinase in forebrain to further characterize the role of this non-receptor tyrosine kinase in the mediation of ethanol sensitivity. Transgenic mice over-expressing fyn-kinase were tested for sensitivity to ethanol-induced loss of righting reflex and ethanol preference drinking using a two-bottle choice drinking paradigm. Loss of righting reflex induced by 4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol (THIP; GABAA agonist) and etomidate (GABAA positive allosteric modulator) were also assessed. Fyn over-expressing mice exhibited shorter durations of ethanol-induced loss of righting reflex in the absence of differences in the rate of blood ethanol clearance, and exhibited reduced ethanol preference drinking. The genotypes did not differ in initial sensitivity to ethanol-induced loss of righting reflex suggesting development of greater acute tolerance to this ethanol action. Fyn over-expressing and wild-type mice also did not differ in sensitivity to loss of righting reflex induced by THIP and etomidate. The present results suggest regional specificity for fyn-kinase in the modulation of ethanol and GABAergic behavioral sensitivity. Fyn-kinase over-expression in forebrain structures modulates ethanol's hypnotic actions, as well as ethanol preference and consumption. Moreover, fyn over-expression in forebrain does not alter hypnotic sensitivity to THIP or etomidate, supporting data from fyn null mutant mice suggesting that cerebellar structures mediate the hypnotic actions of these GABAergic compounds.
Keywords: Behavior; Ethanol; Fyn-kinase; Transgenic mouse

Pharmacogenetic studies of alcohol self-administration and withdrawal - Crabbe, John C.; Phillips, Tamara J. (Psychopharmacology, 2004)
Keywords: alcoholism; Alcohols; Animal; Animals; Disease Models; Humans; Models; Molecular; Pharmacogenetics; Quantitative Trait Loci; Risk Factors; Self Administration; Substance Withdrawal Syndrome

Recent advances in animal models of alcohol craving and relapse - Rodd, Zachary A.; Bell, Richard L.; Sable, Helen J. K.; Murphy, James M.; McBride, William J. (Pharmacology, Biochemistry, and Behavior, 2004)
Animal models designed to examine different facets of alcohol-related behaviors have been developed to study genetic and neurobiological factors underlying alcoholism and alcohol abuse. One goal has been to develop valid, congruent, complementary animal models of alcohol craving and relapse, with the ultimate objective of assessing the effectiveness of pharmacological agents with these models. Animal models of alcohol craving include drug-induced responding (drug reinstatement), cue-induced responding, Pavlovian Spontaneous Recovery (PSR), and appetitive/consummatory responding. A primary experimental approach to study alcohol relapse has been through expression of the Alcohol Deprivation Effect (ADE) following a single deprivation or multiple deprivations. To date, five selectively bred lines of rats have been developed to study alcohol-drinking behavior. These are the ALKO/Alcohol (AA), alcohol-preferring (P), high alcohol-drinking (HAD-1 and HAD-2 replicates), and the Sardinian alcohol-preferring (sP) lines of rats. Findings thus far indicate that only the P line of rats meets all the criteria established for a valid animal model of alcoholism, with progress having been made in characterizing the AA, HAD and sP lines of rats. The focus of the current review will be to analyze the various models of alcohol craving, emphasizing the use of the Indiana University selected rat lines (P and HADs). Overall, the findings indicate substantial progress has been made in developing animal models of alcohol abuse, relapse and craving using these selectively bred rat lines, as well as outbred rats.
Keywords: Alcohol Drinking; alcoholism; Animal; Animals; Disease Models; Humans; Rats; Secondary Prevention

Recent advances in cyclic-adenosine monophosphate/protein kinase A signaling in ethanol-induced synaptic and behavioral alterations - Chandler, L. Judson; Bonci, Antonello; Wand, Gary S.; Morrisett, Richard A. (Alcoholism, Clinical and Experimental Research, 2004)
This article represents the proceedings of a symposium at the 2002 RSA Meeting in San Francisco, California, organized and co-chaired by L. Judson Chandler and Richard A. Morrisett. The presentations were (1) PKA regulates chronic ethanol-induced synaptic targeting of NMDA receptors, by L. Judson Chandler; (2) Long-lasting potentiation of GABAergic synapses in dopamine neurons after a single in vivo ethanol exposure, by Antonello Bonci; (3) The DARPP-32 cascade and regulation of the ethanol sensitivity of NMDA receptors in the nucleus accumbens, by Richard A. Morrisett; (4) and The cAMP/PKA signal transduction pathway modulates ethanol consumption and sedative effects of ethanol, by Gary S. Wand.
Keywords: Animals; Cyclic AMP-Dependent Protein Kinases; Ethanol; Signal Transduction; Synapses

Reduced neuropeptide Y mRNA expression in the central nucleus of amygdala of alcohol preferring (P) rats: its potential involvement in alcohol preference and anxiety - Suzuki, Ryoji; Lumeng, Lawrence; McBride, William J.; Li, Ting-Kai; Hwang, Bang H. (Brain Research, 2004)
Levels of neuropeptide Y (NPY) mRNA expression in discrete brain regions of alcohol preferring (P) rats and alcohol nonpreferring (NP) rats were examined using in situ hybridization. NPY mRNA expression was significantly lower in the central nucleus of amygdala (CeA) of P rats than NP rats, whereas no differences were found in the medial or basolateral amygdaloid nuclei. This study suggests that reduced NPY gene expression in the CeA may contribute to differences in alcohol preference and other behavioral differences observed between P and NP rats.
Keywords: Alcohol Drinking; Amygdala; Animals; Anxiety; Base Sequence; Gene Expression; Genetic; In Situ Hybridization; Male; Messenger; Neuropeptide Y; Phenotype; Protein Biosynthesis; Rats; RNA; Transcription

Sex differences in the effect of ethanol injection and consumption on brain allopregnanolone levels in C57BL/6 mice - Finn, D. A.; Sinnott, R. S.; Ford, M. M.; Long, S. L.; Tanchuck, M. A.; Phillips, T. J. (Neuroscience, 2004)
The pharmacological profile of allopregnanolone, a neuroactive steroid that is a potent positive modulator of gamma-aminobutyric acidA (GABAA) receptors, is similar to that of ethanol. Recent findings indicate that acute injection of ethanol increased endogenous allopregnanolone to pharmacologically relevant concentrations in male rats. However, there are no comparable data in mice, nor has the effect of ethanol drinking on endogenous allopregnanolone levels been investigated. Therefore, the present studies measured the effect of ethanol drinking and injection on allopregnanolone levels in male and female C57BL/6 mice. One group was given 17 days of 2-h limited access to a 10% v/v ethanol solution in a preference-drinking paradigm, while another group had access to water only. The ethanol dose consumed in 2 h exceeded 2 g/kg. Then, separate groups of mice were injected with either 2 g/kg ethanol or saline. Mice were killed 30 min after the 2-h drinking session or injection. Blood ethanol concentration was significantly higher in the ethanol-injected versus ethanol-drinking groups, even though the dose was similar. Consumption of ethanol significantly increased brain allopregnanolone levels in male but not female mice, compared with animals drinking water, but did not alter plasma corticosterone levels. In contrast, injection of ethanol did not significantly alter brain allopregnanolone levels in male or female mice and only significantly increased plasma corticosterone levels in the male mice, when compared with saline-injected animals. The sex differences in the effect of ethanol administration on endogenous allopregnanolone levels suggest that the hormonal milieu may impact ethanol's effect on GABAergic neurosteroids. Importantly, these data are the first to report the effect of ethanol drinking on allopregnanolone levels and indicate that ethanol consumption and ethanol injection can produce physiologically relevant allopregnanolone levels in male mice. These results have important implications for studies investigating the potential role of endogenous allopregnanolone levels in modulating susceptibility to ethanol abuse.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Brain; Brain Chemistry; Central Nervous System Depressants; Chromatography; Corticosterone; Dose-Response Relationship; Drug; Drug Administration Routes; Ethanol; Female; Gas; Inbred C57BL; Injections; Male; Mice; Pregnanolone; Radioimmunoassay; Sex Characteristics

Sindbis viral-mediated expression of eGFP-dopamine D1 receptors in situ with real-time two-photon microscopic detection - Diaz, Laurea M.; Maiya, Rajani; Sullivan, Matthew A.; Han, Yunqing; Walton, Heather A.; Boehm, Stephen L.; Bergeson, Susan E.; Mayfield, R. Dayne; Morrisett, Richard A. (Journal of Neuroscience Methods, 2004)
Dopamine D1 receptors (D1DRs) mediate a major component of dopaminergic neurotransmission, and alterations in their synaptic and subcellular distribution may underlie a variety of neurological diseases. In order to monitor D1DR localization in real time, we subcloned a sindbis virus containing an enhanced-GFP coding region inserted at the C-terminal region of a dopamine D1 receptor (eGFP-D1DR). Two-photon excitation of expressed eGFP-D1DRs was monitored in a variety of viable neural preparations. Infection of primary cultured rat ventral striatal neurons, verified for neuronal phenotype using patch clamp electrophysiology, was induced by the simple addition of the virus to media. Parasagittal slice cultures, including the ventral tegmental area (VTA) and nucleus accumbens (NAc), were infected by manual injection below the glia surface. NAc-containing parasagittal slices prepared from mice in which the virus was administered via stereotaxic injection in vivo also displayed robust eGFP-D1DR expression. Expression of functional D1DRs following infection in baby hamster kidney (BHK) cells was monitored by DA-stimulated cAMP production that was also blocked by a selective D1 antagonist. Taken together, these findings provide the first demonstration of the functional expression and real-time imaging of eGFP-D1DRs, and indicate that sindbis virus is an effective method for D1 receptor expression in a variety of native neuronal preparations.
Keywords: Animals; Cell Line; Cells; Cloning; Computer Systems; Cricetinae; Cultured; Dopamine D1; Fluorescence; Green Fluorescent Proteins; In Vitro Techniques; Microscopy; Molecular; Multiphoton; Neurons; Rats; Receptors; Sindbis Virus; Sprague-Dawley

Use of Selectively Bred Alcohol-Preferring Rats to Study Alcohol Abuse, relapse and Craving - Bell, Richard L.; Rodd, Z. A.; Murphy, James M.; McBride, William J. (2004)

Blood alcohol concentrations after scheduled access in high-alcohol-preferring mice - Grahame, Nicholas J.; Grose, Amanda M. (Alcohol (Fayetteville, N.Y.), 2003)
Development of procedures yielding substantial blood alcohol concentrations during voluntary access to an alcohol solution in mice is necessary to further characterize genetic and neurobiologic mechanisms underlying alcohol self-administration. Although, in experimental situations, some populations of mice readily drink an alcohol solution, results from previous studies have not typically revealed high blood alcohol concentrations after voluntary access, probably because of the high alcohol metabolism rate in mice. Toward development of a murine drinking model, 36 selectively bred high-alcohol-preferring mice of both sexes were subjected to a 30-min scheduled-access procedure by using saccharin fading to gradually introduce an alcohol solution. Mice had ad libitum access to food and water 24 h a day. The alcohol solution was available 1 h after the start of the dark part of the cycle for 30 min per day, 5 days per week. After complete removal of saccharin from the drinking tubes, mice consistently drank 1.4 g/kg of a 10% [volume/volume (vol./vol.)] alcohol solution in 30 min. Analysis of tail blood samples, taken immediately after the end of the 30-min access period, indicated blood alcohol concentrations were tightly correlated with alcohol intakes (range, 6-130 mg/dl; average, nearly 60 mg/dl). A concentration-response function of 10%, 12%, 15%, 18%, and 21% (vol./vol.) alcohol solutions indicated an inverted U-shaped relation between alcohol intake and alcohol concentration, with peak intake of greater than 1.75 g/kg per 30 min when a 15% alcohol solution was available. No sex differences were seen. These findings indicate the utility of this procedure in obtaining pharmacologically relevant blood alcohol concentrations after voluntary oral self-administration of an alcohol solution in mice.
Keywords: Alcohol Drinking; Animals; Dose-Response Relationship; Drug; Ethanol; Female; Male; Mice; Species Specificity

Chromosomal loci influencing chronic alcohol withdrawal severity - Bergeson, Susan E.; Warren, R. Kyle; Crabbe, John C.; Metten, Pamela; Erwin, V. Gene; Belknap, John K. (Mammalian Genome, 2003)
Ethanol (alcohol) withdrawal-induced convulsions are a key index of physical dependence on ethanol and a clinically important consequence of alcohol abuse in humans. In rodent models, severity of withdrawal is strongly influenced by genotype. For example, many studies have reported marked differences in withdrawal severity between the WSR (Withdrawal Seizure Resistant) and WSP (Withdrawal Seizure Prone) mouse strains selectively bred for over 25 generations to differ in chronic withdrawal severity. Therefore, we used an F2 intercross between the inbred WSP and WSR strains for a genome-wide search for quantitative trait loci (QTLs), which are chromosomal sites containing genes influencing the magnitude of withdrawal. We also used the recently developed HW, RHW (high withdrawal) and LW, RLW (low withdrawal) lines selectively bred for the same trait and in the same manner as the WSP, WSR lines. QTL analysis was then used to dissect the continuous trait distribution of withdrawal severity into component loci, and to map them to broad chromosomal regions by using the Pseudomarker 0.9 and Map Manager QT29b programs. This genome-wide search identified five significant QTLs influencing chronic withdrawal severity on Chromosomes (Chrs) 1 (proximal), 4 (mid), 8 (mid), 11 (proximal), and 14 (mid), plus significant interactions (epistasis) between loci on Chr 11 with 13, 4 with 8, and 8 with 14.

Current Strategies for Identifying Genes for Alcohol Sensitivity - Crabbe, John C. (Molecular Biology of Drug Addiction, 2003)
The familial occurrence of alcoholism has been known for many years. Many twin, adoption, and family studies now concur that this familial pattern is to a great extent conferred by genes transmitted to biological offspring (1,2). Approximately 50–60% of individual differences in risk for alcoholism is genetic, and this proportion is approximately equal in men and women (2). Thus, it is an easy task to predict that a close biological relative of an alcoholic is at higher risk for alcoholism. However, risk is not inherited alleles at specific risk-promoting or -protective genes are inherited. To date, there are only two specific genes known to confer substantial protection against alcoholism, variants at the ALDH2*2 and ADH2*2 metabolic enzymes. The variant alleles lead to the accumulation of alcohol’ s metabolite, acetaldehyde, when susceptible individuals drink alcohol. This toxic compound produces nausea, flushing, dizziness, and other unpleasant effects, and slow alcohol metabolizers avoid excessive drinking (3). Therefore, progress from assigning risk statistically to ascertaining whether specific individuals possess risk-promoting or -protective alleles will require the identification of the specific genes underlying risk.
Keywords: Neurosciences

Deletion of the alpha1 or beta2 subunit of GABAA receptors reduces actions of alcohol and other drugs - Blednov, Yuri A.; Jung, S.; Alva, H.; Wallace, D.; Rosahl, T.; Whiting, P.-J.; Harris, R. Adron (The Journal of Pharmacology and Experimental Therapeutics, 2003)
Enhancement of the activation of GABAA receptors is a common feature of many sedative and hypnotic drugs, and it is probable that the GABAA receptor complex is a molecular target for these drugs in the mammalian central nervous system. We set out to elucidate the role of the two predominant (alpha1 and beta2) subunits of GABAA receptor in sedative drug action by studying mice lacking these two subunits. Both alpha1 (-/-) and beta2 (-/-) null mutant mice showed markedly decreased sleep time induced by nonselective benzodiazepine, flurazepam, and GABAA agonist, 4,5,6,7-tetrahydroisoxazolo(5,4-c)pyridin-3-ol. The sleep time induced by the beta-selective drug etomidate was decreased only in beta2 (-/-) knockout mice. In contrast, alpha1 (-/-) mice were more resistant to the alpha1-selective drug zolpidem than beta2 (-/-) or wild-type animals. Knockout mice of both strains were similar to wild-type mice in their responses to pentobarbital. The duration of loss of the righting reflex produced by ethanol was decreased in male mice for both null alleles compared with wild-type mice, but there were no differences in ethanol-induced sleep time in mutant females. Deletion of either the alpha1 or beta2 subunits reduced the muscimol-stimulated 36Cl36 influx in cortical microsacs suggesting that these mutant mice have reduced number of functional brain GABAA receptors. Our results show that removal of either alpha1 or beta2 subunits of GABAA receptors produce strong and selective decreases in hypnotic effects of different drugs. Overall, these data confirm the crucial role of the GABAA receptor in mechanisms mediating sedative/hypnotic effects.
Keywords: Animal; Animals; Behavior; Brain; Central Nervous System Depressants; Chlorides; Ethanol; Etomidate; Female; Flurazepam; GABA; GABA Agonists; GABA Modulators; GABA-A; Gene Deletion; Hypnotics and Sedatives; Isoxazoles; Knockout; Male; Mice; Pentobarbital; Postural Balance; Pyridines; Receptors; Sex Characteristics; Sleep; Time Factors

Deletion of the fyn-kinase gene alters behavioral sensitivity to ethanol - Boehm, Stephen L.; Peden, Laura; Chang, Rose; Harris, R. Adron; Blednov, Yuri A. (Alcoholism, Clinical and Experimental Research, 2003)
BACKGROUND: An earlier study showed that deletion of the fyn-kinase gene enhanced sensitivity to ethanol's sedative hypnotic effects and suggested that this was associated with diminished fyn-kinase phosphorylation of NMDA receptors. The authors of that study speculated that this resulted in an inability of the null mutants to develop acute tolerance to ethanol, leading to the longer ethanol-induced sleep times. However, in vivo acute tolerance to ethanol was not examined directly. METHODS: To address the role of fyn-kinase in mediating acute tolerance, as well as sensitivity to several other behavioral effects of ethanol, we studied an independently generated population of fyn null mutant and wild-type mice. RESULTS: Homozygous mutants exhibited longer ethanol sleep times that could not be attributed to differences in initial sensitivity, and impaired acute tolerance to the motor incoordinating effects of ethanol as measured by using the stationary dowel, but not the rotarod. Fyn-kinase null mutants were more sensitive to the anxiolytic effects of ethanol when tested using the elevated plus maze, and males displayed a lower preference for ethanol in a two-bottle choice paradigm. Finally, mutant and wild-type mice did not differ in sensitivity to the hypothermic effects of ethanol. The genotypes also did not differ in blood-ethanol clearance, eliminating a metabolic explanation for these behavioral differences. CONCLUSIONS: These results show that fyn-kinase modulates acute tolerance to ethanol and suggest a role for fyn in mediating ethanol's anxiolytic and reinforcing properties.
Keywords: Addictive; Animals; Behavior; Ethanol; Exploratory Behavior; Female; Gene Deletion; Knockout; Male; Mice; Motor Skills; Neoplasm Proteins; Protein-Tyrosine Kinases; src-Family Kinases

The Edinger-Westphal–Lateral Septum Urocortin Pathway and Its Relationship to Alcohol Consumption - Bachtell, Ryan K.; Weitemier, Adam Z.; Galvan-Rosas, Agustin; Tsivkovskaia, Natalia O.; Risinger, Fred O.; Phillips, Tamara J.; Grahame, Nicholas J.; Ryabinin, Andrey E. (Journal of Neuroscience, 2003)
Identifying and characterizing brain regions regulating alcohol consumption is beneficial for understanding the mechanisms of alcoholism. To this aim, we first identified brain regions changing in expression of the inducible transcription factor c-Fos in the alcohol-preferring C57BL/6J (B6) and alcohol-avoiding DBA/2J (D2) mice after ethanol consumption. Drinking a 5% ethanol/10% sucrose solution in a 30 min limited access procedure led to induction of c-Fos immunoreactivity in urocortin (Ucn)-positive cells of the Edinger-Westphal nucleus (EW), suppression of c-Fos immunoreactivity in the dorsal portion of the lateral septum (LS) of both strains of mice, and strain-specific suppression in the intermediate portion of the LS and the CA3 hippocampal region. Because the EW sends Ucn projections to the LS, and B6 and D2 mice differ dramatically in EW Ucn expression, we further analyzed the Ucn EW–LS pathway using several genetic approaches. We find that D2 mice have higher numbers of Ucn-immunoreactive processes than B6 mice in the LS and that consumption of ethanol/sucrose in the F2 offspring of a B6D2 intercross positively correlates with Ucn immunoreactivity in the EW and negatively correlates with Ucn immunoreactivity in the LS. In agreement with these findings, we find that alcohol-avoiding male B6.D2Alcp1 line 2.2 congenic mice have lower Ucn immunoreactivity in the EW than male B6.B6 mice. Finally, we also find that HAP mice, selectively bred for high alcohol preference, have higher Ucn immunoreactivity in EW, than LAP mice, selectively bred for low alcohol preference. Taken together, these studies provide substantial evidence for involvement of the EW–LS Ucn pathway in alcohol consumption.
Keywords: Edinger-Westphal; Ethanol; inducible transcription factor; self-administration; septum; urocortin

Effects of concurrent access to a single concentration or multiple concentrations of ethanol on the intake of ethanol by male and female periadolescent alcohol-preferring (P) rats - Bell, Richard L.; Rodd-Henricks, Zachary A.; Kuc, Kelly A.; Lumeng, Lawrence; Li, Ting Kai; Murphy, James M.; McBride, William J. (Alcohol (Fayetteville, N.Y.), 2003)
The objectives of this study were to assess the effects of access to different concentrations of ethanol and sex of the animal on ethanol consumption during periadolescence [postnatal days (PNDs) 30-60] in alcohol-preferring (P) rats. On PND 28, female and male P pups were single housed in hanging stainless steel cages with ad libitum access to water and food. Beginning on PND 30, the rats were also given access to either a single concentration [15% volume/volume (vol./vol.)] or multiple concentrations [10%, 20%, and 30% (vol./vol.)] of ethanol. Differences between sex (male vs. female) and ethanol conditions (single concentration vs. multiple concentrations), for the average amount of ethanol consumed for each week (starting on PND 33) of access, were examined. Analyses of the data for ethanol drinking revealed significant (P<.025) main effects of week and ethanol condition, as well as a significant weekxethanol condition interaction. For the first week, both male and female P pups consumed more ethanol under the multiple-ethanol-concentration condition than under the single-ethanol-concentration condition. However, across the second through fourth weeks, this pattern was seen only in female P pups. When preference for one concentration of ethanol over the other concentrations was assessed, it was found that male P pups tended to choose the 30% concentration over the 10% and 20% concentrations, whereas female P pups did not display a preference. The findings of this study corroborate previous work indicating that periadolescent P rats readily acquire high-ethanol-drinking behavior and that, similar to adult P rats, concurrent access to multiple concentrations of ethanol further enhances ethanol intake. These findings suggest to us that innate genetically influenced mechanisms promoting high ethanol intake are present at this stage of development.
Keywords: Aging; Alcohol Drinking; Alcoholic Beverages; Animals; Body Weight; Central Nervous System Depressants; Drinking; Ethanol; Female; Male; Rats; Sex Characteristics

Effects of repeated alcohol deprivations on operant ethanol self-administration by alcohol-preferring (P) rats - Rodd, Zachary A.; Bell, Richard L.; Kuc, Kelly A.; Murphy, James M.; Lumeng, Lawrence; Li, Ting-Kai; McBride, William J. (Neuropsychopharmacology: Official Publication of the American College of Neuropsychopharmacology, 2003)
We reported that repeated alcohol deprivations prolonged the expression of an alcohol-deprivation effect (ADE) under 24-h free-choice alcohol-drinking access and that the duration of the initial deprivation period had a positive effect of prolonging the duration of the ADE. In the present study, operant techniques (including progressive ratio measures) were used to examine the effects of initial deprivation length and number of deprivation cycles on the magnitude and duration of the ADE in alcohol-preferring (P) rats to test the hypothesis that repeated deprivations can increase the reinforcing effects of ethanol (ETOH). Adult male P rats were trained in two-lever operant chambers to self-administer 15% ETOH (v/v) on a fixed-ratio 5 (FR-5) and water on a FR-1 schedule of reinforcement in daily 1-h sessions. Following 6 weeks of daily 1-h sessions, the P rats were randomly assigned to one of four groups (n=10/group): nondeprived or deprived of alcohol for 2, 5, or 8 weeks. Following this initial period, the deprived groups were given 15% ETOH again in the operant chambers for a 2-week period, following which they were deprived again for 2 weeks (all three deprived groups). Following the fourth deprivation, the rats underwent a progressive ratio test to determine the breakpoints (FR values) for the nondeprived and the deprived groups. Repeated deprivations increased both the magnitude and duration of the ADE as indicated by increased responding on the ETOH lever. However, the length of the initial deprivation had little effect on expression of the ADE except following the first deprivation, where an ADE was not observed for the 8-week group. Breakpoint values for responding on the ETOH lever for all three deprived groups were two-fold higher than the value for the nondeprived group. The results suggest that repeated cycles of alcohol deprivation and alcohol access increased the reinforcing effects of ETOH in the P rats.
Keywords: Addictive; Alcohol Drinking; Animals; Behavior; Central Nervous System Depressants; Conditioning; Dose-Response Relationship; Drug; Drug Administration Schedule; Ethanol; Food Preferences; Inbred Strains; Male; Motivation; Operant; Rats; Self Administration; Time Factors

Ethanol increases extracellular dopamine concentration in the ventral striatum in C57BL/6 mice - Tang, Amanda; George, Magnia A.; Randall, Judith A.; Gonzales, Rueben A. (Alcoholism, Clinical and Experimental Research, 2003)
BACKGROUND: Mesolimbic dopamine is thought to play a role in the reinforcing properties of ethanol, but ethanol-induced changes in extracellular dopamine in the ventral striatum have not been well characterized in mouse models. METHODS: Two experiments were used to characterize the pharmacodynamic response of ethanol in the ventral striatum in C57BL/6 mice. The first experiment determined the effect of ethanol on ventral striatal dopamine in male and female mice after intraperitoneal injection of either 2.0 g/kg ethanol or saline. The second experiment was a replication in males, except that the mice were habituated to intraperitoneal injections before the dialysis experiment. RESULTS: Distinct patterns of dopamine activity in response to ethanol were demonstrated in male and female C57BL/6 mice. A significant increase in dialysate dopamine relative to saline injection was observed in females but not in males. With habituation to intraperitoneal injection before the dialysis experiment, ethanol administration caused a significant dopamine response in males as well. A linear decline was observed in dialysate ethanol concentrations after the peak concentration was reached. Concurrent analysis of the time course of dopamine and ethanol content showed that the dopamine response declined significantly faster than the ethanol concentrations. CONCLUSIONS: The C57BL/6 mouse strain is a justifiable model system for studying the mechanisms involved in ethanol regulation of mesolimbic dopamine activity. Habituation to intraperitoneal injection should be used in male C57BL/6 mice for experiments in which the dopamine response is measured after intraperitoneal injection of a drug. The dissociation between dopamine and ethanol may indicate an acute neural adaptation to ethanol-induced dopamine response in the ventral striatum after a single ethanol injection.
Keywords: Animals; Basal Ganglia; dopamine; Ethanol; Extracellular Fluid; Female; Inbred C57BL; Male; Mice

Ethanol increases GABAergic transmission at both pre- and postsynaptic sites in rat central amygdala neurons - Roberto, Marisa; Madamba, Samuel G.; Moore, Scott D.; Tallent, Melanie K.; Siggins, George R. (Proceedings of the National Academy of Sciences of the United States of America, 2003)
We examined the interaction of ethanol with the gamma-aminobutyric acid (GABA)ergic system in neurons of slices of the rat central amygdala nucleus (CeA), a brain region thought to be critical for the reinforcing effects of ethanol. Brief superfusion of 11-66 mM ethanol significantly increased GABA type A (GABA(A)) receptor-mediated inhibitory postsynaptic potentials (IPSPs) and currents (IPSCs) in most CeA neurons, with a low apparent EC(50) of 20 mM. Acute superfusion of 44 mM ethanol increased the amplitude of evoked GABA(A) IPSPs and IPSCs in 70% of CeA neurons. The ethanol enhancement of IPSPs and IPSCs occurred to a similar extent in the presence of the GABA type B (GABA(B)) receptor antagonist CGP 55845A, suggesting that this receptor is not involved in the ethanol effect on CeA neurons. Ethanol superfusion also decreased paired-pulse facilitation of evoked GABA(A) IPSPs and IPSCs and always increased the frequency and sometimes the amplitude of spontaneous miniature GABA(A) IPSCs as well as responses to local GABA application, indicating both presynaptic and postsynaptic sites of action for ethanol. Thus, the CeA is the first brain region to reveal, without conditional treatments such as GABA(B) antagonists, consistent, low-dose ethanol enhancement of GABAergic transmission at both pre- and postsynaptic sites. These findings add further support to the contention that the ethanol-GABA interaction in CeA plays an important role in the reinforcing effects of ethanol.
Keywords: Amygdala; Animals; Ethanol; Evoked Potentials; gamma-Aminobutyric Acid; In Vitro Techniques; Neurons; Patch-Clamp Techniques; Rats; Sprague-Dawley; Synaptic Transmission

Finding genes for complex behaviors: Progress in mouse models of the addictions - Crabbe, John C. (Behavioral genetics in the postgenomic era, 2003)
The goal of this chapter is to focus on recent advances in identifying specific genes and their function in mouse models of the addictions, concentrating on quantitative trait loci (QTL) mapping and the alternative strategy of randomly induced mutagenesis. This approach recognizes that individuals may differ because of differences in the expression of genes as well rather than in the structure of their coded protein. Gene expression arrays are just beginning to be used as a gene discovery tool, and the limited data available are discussed. Finally, candidate gene studies using transgenic technologies to over- or underexpress specific genes in mice are mentioned. Throughout the chapter, the author pleads the case for a behavioral genomics approach to understanding gene function, which depends on the careful analysis of phenotypic variation in its environmental context and on the rigorous mapping of specific behaviors to the psychological constructs they are intended to represent.
Keywords: *Animal Models; *Behavioral Genetics; *Drug Addiction; *Genetic Linkage; Genes; Mice; Phenotypes

GABAA receptor alpha 1 and beta 2 subunit null mutant mice: behavioral responses to ethanol - Blednov, Y. A.; Walker, D.; Alva, H.; Creech, K.; Findlay, G.; Harris, R. A. (The Journal of Pharmacology and Experimental Therapeutics, 2003)
Mice lacking either the alpha1 or beta 2 subunit of the GABAA receptor were tested for ethanol, saccharin, or quinine consumption, ethanol-conditioned place preference, ethanol-conditioned taste aversion, ethanol-simulated motor activity, and handling-induced seizures following chronic consumption of an ethanol liquid diet. The alpha1 null mutants showed decreased ethanol and saccharin consumption, increased aversion to ethanol, and a marked stimulation of motor activity after injection of ethanol. The beta 2 null mutants showed decreased consumption of saccharin and quinine, but not ethanol. Surprisingly, neither mutant showed marked changes in handling induced seizures before or after withdrawal of ethanol. The unique effects of deletion of these two GABAA receptor subunits on ethanol responses are discussed in terms of the distinct changes in different populations of GABAA receptors.
Keywords: Alcohol Drinking; Animal; Animals; Behavior; Central Nervous System Depressants; Classical; Conditioning; Ethanol; Female; GABA-A; Inbred C57BL; Knockout; Mice; Motor Activity; Receptors

Gene expression in brain: a window on ethanol dependence, neuroadaptation, and preference - Hoffman, Paula L.; Miles, Michael; Edenberg, Howard J.; Sommer, Wolfgang; Tabakoff, Boris; Wehner, Jeanne M.; Lewohl, Joanne (Alcoholism, Clinical and Experimental Research, 2003)
This article represents the proceedings of a symposium at the 2002 joint RSA/ISBRA Conference in San Francisco, California. The organizer was Paula L. Hoffman and the co-chairs were Paula L. Hoffman and Michael Miles. The presentations were (1) Introduction and overview of the use of DNA microarrays, by Michael Miles; (2) DNA microarray analysis of gene expression in brains of P and NP rats, by Howard J. Edenberg; (3) Gene expression patterns in brain regions of AA and ANA rats, by Wolfgang Sommer; (4) Patterns of gene expression in brains of selected lines of mice that differ in ethanol tolerance, by Boris Tabakoff; (5) Gene expression profiling related to initial sensitivity and tolerance in gamma-protein kinase C mutants, by Jeanne Wehner; and (6) Gene expression patterns in human alcoholic brain: from microarrays to protein profiles, by Joanne Lewohl.
Keywords: Alcohol Drinking; alcoholism; Animals; Brain; Choice Behavior; Drug Tolerance; Gene Expression Profiling; Gene Expression Regulation; Genetic; Humans; Mice; Mutant Strains; Oligonucleotide Array Sequence Analysis; Protein Kinase C; Rats; Selection; Transgenic

Genetic animal models of anxiety - Finn, Deborah A.; Rutledge-Gorman, Mark T.; Crabbe, John C. (Neurogenetics, 2003)
The focus of this review is on progress achieved in identifying specific genes conferring risk for anxiety disorders through the use of genetic animal models. We discuss gene-finding studies as well as those manipulating a candidate gene. Both human and animal studies thus far support the genetic complexity of anxiety. Clinical manifestations of these diseases are likely related to multiple genes. While different anxiety disorders and anxiety-related traits all appear to be genetically influenced, it has been difficult to ascertain genetic influences in common. Mouse studies have provisionally mapped several loci harboring genes that affect anxiety-related behavior. The growing array of mutant mice is providing valuable information about how genes and environment interact to affect anxious behavior via multiple neuropharmacological pathways. Classical genetic methods such as artificial selection of rodents for high or low anxiety are being employed. Expression array technologies have as yet not been employed, but can be expected to implicate novel candidates and neurobiological pathways.
Keywords: Animal; Animals; Anxiety; Anxiety Disorders; Diseases in Twins; Female; Genetic Linkage; Genetic Predisposition to Disease; Humans; Hypothalamo-Hypophyseal System; Inbreeding; Knockout; Male; Membrane Transport Proteins; Mice; Models; Mutagenesis; Nerve Tissue Proteins; Neurotransmitter; Neurotransmitter Agents; Oligonucleotide Array Sequence Analysis; Quantitative Trait Loci; Rats; Receptors; Transgenic

Glutamatergic transmission in opiate and alcohol dependence - Siggins, George Robert; Martin, Gilles; Roberto, Marisa; Nie, Zhiguo; Madamba, Samuel; De Lecea, Luis (Annals of the New York Academy of Sciences, 2003)
Both the nucleus accumbens (NAcc) and central amygdala (CeA) are thought to play roles in tolerance to, and dependence on, abused drugs. Although our past studies in rat brain slices suggested a role for NMDA receptors (NMDARs) in NAcc neurons in the effects of acute and chronic opiate treatment, the cellular and molecular mechanisms remained unclear. Therefore, we examined the effects of morphine dependence on electrophysiological properties of NMDARs in freshly isolated NAcc neurons and on expression of mRNA coding for NR2A-C subunits using single-cell RT-PCR. Chronic morphine did not alter the affinity for NMDAR agonists glutamate, homoquinolinate, or NMDA, but decreased the affinity of the coagonist glycine. Chronic morphine altered the NMDAR inhibition by two NMDAR antagonists, 7-Cl-kynurenate and ifenprodil, but not that by d-APV or Mg2+. Chronic morphine accelerated the NMDA current desensitization rate in NAcc neurons. In single-cell RT-PCR, chronic morphine predominantly reduced the number of neurons expressing multiple NR2 subunits. Ethanol also alters NMDARs. We found that low ethanol concentrations (IC50 = 13 mM) inhibited NMDA currents and NMDA-EPSPs in most NAcc neurons in a slice preparation. NAcc neurons from ethanol-dependent rats showed enhanced NMDA sensitivity. In CeA neurons, acute ethanol decreased (by 10-25%) non-NMDA- and NMDA-EPSPs in most neurons. In CeA neurons from ethanol-dependent rats, acute ethanol decreased the non-NMDA-EPSPs to the same extent as in naïve rats, but inhibited (by 30-40%) NMDA-EPSPs significantly more than in controls, suggesting sensitization to ethanol. Preliminary studies with microdialysis and real-time PCR analysis support this idea: local ethanol administration in vivo had no effect on glutamate release, but chronic ethanol nearly tripled the expression of NR2B subunits (the most ethanol sensitive) in CeA. These combined findings suggest that changes in glutamatergic transmission in NAcc and CeA may underlie the neuroadaptions that lead to opiate and ethanol dependence.
Keywords: alcoholism; Amygdala; Animals; Ethanol; Glutamates; Glycine; Humans; Morphine Dependence; N-Methyl-D-Aspartate; Neurons; Nucleus Accumbens; Opioid-Related Disorders; Rats; Receptors; Synaptic Transmission

Glycine Receptor Knock-In Mice and Hyperekplexia-Like Phenotypes: Comparisons with the Null Mutant - Findlay, Geoffrey S.; Phelan, Rachel; Roberts, Michael T.; Homanics, Gregg E.; Bergeson, Susan E.; Lopreato, Gregory F.; Mihic, S. John; Blednov, Yuri A.; Harris, R. Adron (Journal of Neuroscience, 2003)
Strychnine-sensitive glycine receptors (GlyRs) inhibit neurotransmission in the spinal cord and brainstem. To better define the function of this receptor in vivo, we constructed a point mutation that impairs receptor function in the α1-subunit and compared these knock-in mice to oscillator (spdot) mice lacking functional GlyR α1-subunits. Mutation of the serine residue at amino acid 267 to glutamine (α1S267Q) results in a GlyR with normal glycine potency but decreased maximal currents, as shown by electrophysiological recordings using Xenopus oocytes. In addition, single-channel recordings using human embryonic kidney 293 cells indicated profoundly altered properties of the mutated GlyR. We produced knock-in mice bearing the GlyR α1 S267Q mutation to assess the in vivo consequences of selectively decreasing GlyR efficacy. Chloride uptake into brain synaptoneurosomes from knock-in mice revealed decreased responses to maximally effective glycine concentrations, although wild-type levels of GlyR expression were observed using 3H-strychnine binding and immunoblotting. A profound increase in the acoustic startle response was observed in knock-in mice as well as a “limb clenching” phenotype. In contrast, no changes in coordination or pain perception were observed using the rotarod or hot-plate tests, and there was no change in GABAA-receptor-mediated chloride uptake. Homozygous S267Q knock-in mice, like homozygous spdot mice, exhibited seizures and died within 3 weeks of birth. In heterozygous spdot mice, both decreased 3H-strychnine binding and chloride flux were observed; however, neither enhanced acoustic startle responses nor limb clenching were seen. These data demonstrate that a dominant-negative point mutation in GlyR disrupting normal function can produce a more dramatic phenotype than the corresponding recessive null mutation, and provides a new animal model to evaluate GlyR function in vivo.
Keywords: acoustic startle response; channel gating; chloride flux; Glycine; GlyR; hyperekplexia; knock-in; Mice; oscillator; spd-ot; strychnine; Xenopus oocytes

Innate differences in protein expression in the nucleus accumbens and hippocampus of inbred alcohol-preferring and -nonpreferring rats - Witzmann, Frank A.; Li, Junyu; Strother, Wendy N.; McBride, William J.; Hunter, Lawrence; Crabb, David W.; Lumeng, Lawrence; Li, Ting-Kai (PROTEOMICS, 2003)
Two-dimensional gel electrophoresis (2-DE) was used to separate protein samples solubilized from the nucleus accumbens and hippocampus of alcohol-naïve, adult, male inbred alcohol-preferring (iP) and alcohol-nonpreferring (iNP) rats. Several protein spots were excised from the gel, destained, digested with trypsin, and analyzed by mass spectrometry. In the hippocampus, 1629 protein spots were matched to the reference pattern, and in the nucleus accumbens, 1390 protein spots were matched. Approximately 70 proteins were identified in both regions. In the hippocampus, only 8 of the 1629 matched protein spots differed in abundance between the iP and iNP rats. In the nucleus accumbens, 32 of the 1390 matched protein spots differed in abundance between the iP and iNP rats. In the hippocampus, the abundances of all 8 proteins were higher in the iNP than iP rat. In the nucleus accumbens, the abundances of 31 of 32 proteins were higher in the iNP than iP rat. In the hippocampus, only 2 of the 8 proteins that differed could be identified, whereas in the nucleus accumbens 21 of the 32 proteins that differed were identified. Higher abundances of cellular retinoic acid-binding protein 1 and a calmodulin-dependent protein kinase (both of which are involved in cellular signaling pathways) were found in both regions of the iNP than iP rat. In the nucleus accumbens, additional differences in the abundances of proteins involved in (i) metabolism (e.g., calpain, parkin, glucokinase, apolipoprotein E, sorbitol dehydrogenase), (ii) cyto-skeletal and intracellular protein transport (e.g., β-actin), (iii) molecular chaperoning (e.g., grp 78, hsc70, hsc 60, grp75, prohibitin), (iv) cellular signaling pathways (e.g., protein kinase C-binding protein), (v) synaptic function (e.g., complexin I, γ-enolase, syndapin IIbb), (vi) reduction of oxidative stress (thioredoxin peroxidase), and (vii) growth and differentiation (hippocampal cholinergic neurostimulating peptide) were found. The results of this study indicate that selective breeding for disparate alcohol drinking behaviors produced innate alterations in the expression of several proteins that could influence neuronal function within the nucleus accumbens and hippocampus.
Keywords: Alcohol-preferring P rats; Hippocampus; Nucleus Accumbens; Two-dimensional gel electrophoresis

The Longhorn Array Database (LAD): An Open-Source, MIAME compliant implementation of the Stanford Microarray Database (SMD) - Killion, Patrick J; Sherlock, Gavin; Iyer, Vishwanath R (BMC Bioinformatics, 2003)
Background The power of microarray analysis can be realized only if data is systematically archived and linked to biological annotations as well as analysis algorithms. Description The Longhorn Array Database (LAD) is a MIAME compliant microarray database that operates on PostgreSQL and Linux. It is a fully open source version of the Stanford Microarray Database (SMD), one of the largest microarray databases. LAD is available at Conclusions Our development of LAD provides a simple, free, open, reliable and proven solution for storage and analysis of two-color microarray data.

Methods for the identification of differentially expressed genes in human post-mortem brain - Mayfield, R. Dayne; Liu, Jianwen; Randall, Patrick K; Lewohl, Joanne M; Dodd, Peter R; Harris, R. Adron (Candidate Genes from DNA Array Screens: application to neuroscience, 2003)
Microarrays can be used to monitor the expression of thousands of genes simultaneously. This technique requires high-quality RNA which can be extracted from a variety of tissues and cells including post-mortem human brain. Given the vast amount of information obtained from microarray studies, it is critical to establish valid analysis techniques to identify differentially expressed genes. This technical report describes the basic methodology and analyses used to identify such genes in human post-mortem brain tissue.

Neural stem cells and alcohol - Crews, F. T.; Miller, Michael W.; Ma, Wu; Nixon, Kim; Zawada, W. Michael; Zakhari, Sam (Alcoholism, Clinical and Experimental Research, 2003)
This article summarizes the proceedings of a symposium held at the 2002 Research Society on Alcoholism Meeting in San Francisco, California. The aim of this symposium was to review research on the effects of ethanol on neural stems cells and neurogenesis. Ethanol is known to alter neurogenesis during development; however, recent studies indicate that the brain forms new neurons from stem cells throughout life. Furthermore, stem cells can be transplanted into the brain, creating exciting new possibilities to study brain function. The symposium covered these research areas. Dr. Michael W. Miller reviewed knowledge on the effects of ethanol on stem cell proliferation and differentiation during development. Dr. Wu Ma described studies in culture indicating that (1) neural stem cells express functional muscarinic acetylcholine receptors (mAchR), (2) mAchR-mediated proliferation involves Ca signaling and mitogen-activated protein kinase phosphorylation, and (3) phosphoinositol-3 kinase is a downstream effector for mAchR-mediated cell proliferation via activation of Akt. Drs. Kim Nixon and Fulton T. Crews followed with in vivo studies on ethanol's effects on adult neural stem cell proliferation and differentiation. Dr. W. Michael Zawada described studies directed at dopamine neuron cell transplants into mammalian central nervous system. These studies clearly establish that ethanol has significant effects on stem cells.
Keywords: Adult; Animals; Brain Tissue Transplantation; Cell Differentiation; Cell Division; Child; Ethanol; Female; Humans; Muscarinic; Neuroglia; Neurons; Pregnancy; Receptors; Signal Transduction; Stem Cell Transplantation; Stem Cells

New neuronal networks involved in ethanol reinforcement - Kiianmaa, Kalervo; Hyytiä, Petri; Samson, Herman H.; Engel, Jörgen A.; Svensson, Lennart; Söderpalm, Bo; Larsson, Anna; Colombo, Giancarlo; Vacca, Giovanni; Finn, Deborah A.; Bachtell, Ryan K.; Ryabinin, Andrey E. (Alcoholism, Clinical and Experimental Research, 2003)
This article represents the proceedings of a symposium at the 2002 ISBRA/RSA meeting in San Francisco. The organizers were Kalervo Kiianmaa and Andrey E. Ryabinin. The chairs were Kalervo Kiianmaa and Jörgen A. Engel. The presentations were (1) The role of opioidergic and dopaminergic networks in ethanol-seeking behavior, by Kalervo Kiianmaa and Petri Hyytiä; (2) Interaction between the dopamine systems in the prefrontal cortex and nucleus accumbens during ethanol self-administration, by Herman H. Samson; (3) Neurochemical and behavioral studies on ethanol and nicotine interactions, by Jörgen A. Engel, Lennart Svensson, Bo Söderpalm, and Anna Larsson; (4) Involvement of the GABA receptor in alcohol reinforcement in sP rats, by Giancarlo Colombo and Giovanni Vacca; (5) Neuroactive steroids and ethanol reinforcement, by Deborah A. Finn, and (6) Potential contribution of the urocortin system to regulation of alcohol self-administration, by Andrey E. Ryabinin and Ryan K. Bachtell.(B)
Keywords: Alcohol Drinking; alcoholism; Animals; Brain; Brain Mapping; Humans; Neural Networks (Computer); Neurotransmitter Agents; Reinforcement (Psychology)

A pervasive mechanism for analgesia: activation of GIRK2 channels - Blednov, Y. A.; Stoffel, M.; Alva, H.; Harris, R. A. (Proceedings of the National Academy of Sciences of the United States of America, 2003)
G protein-coupled inwardly rectifying potassium channels (GIRKs) provide a common link between numerous neurotransmitter receptors and the regulation of synaptic transmission. We asked whether GIRKs specify a single behavioral action that is produced by drugs acting on the diverse receptors coupled with GIRKs. By using GIRK2-null mutant mice, we found marked reduction or complete elimination of the antinociceptive (hot plate test) effects of ethanol, oxotremorine, nicotine, baclofen, clonidine, and the cannabinoid receptor agonist WIN 55,212. However, ketamine analgesia remained intact. For most drugs, there was a sex difference in antinociceptive action, and the impact of deletion of the GIRK2 channel was less in female mice. The deletion of the GIRK2 channel blocks the opioid-dependent component of stress-induced analgesia (SIA), whereas nonopioid SIA was not changed. We propose that opioid, alpha adrenergic, muscarinic cholinergic, gamma-aminobutyric acid-B, and cannabinoid receptors are coupled with postsynaptic GIRK2 channels in vivo. Furthermore, this pathway accounts for essentially all of the antinociceptive effects in males, although females appear to recruit additional signal transduction mechanisms for some analgesic drugs.
Keywords: Analgesia; Analgesics; Animals; Baclofen; Benzoxazines; Clonidine; Crosses; Ethanol; Female; G Protein-Coupled Inwardly-Rectifying Potassium Channels; Genetic; Inbred C57BL; Inwardly Rectifying; Knockout; Male; Mice; Morpholines; Mutagenesis; Naphthalenes; Nicotine; Oxotremorine; Pain; Polymerase Chain Reaction; Potassium Channels; Sex Characteristics

Reduced ethanol-induced conditioned taste aversion and conditioned place preference in GIRK2 null mutant mice - Hill, Katherine G.; Alva, Herminia; Blednov, Yuri A.; Cunningham, Christopher L. (Psychopharmacology, 2003)
RATIONALE: Previous studies have shown that GIRK2 channel function is enhanced by ethanol and that GIRK2 null mutant mice are less sensitive to some of ethanol's effects, including anxiolysis, habituated locomotor stimulation, and acute handling-induced convulsions than wild types. Under some conditions, GIRK2 knockout mice consume more ethanol than wild types, but it is unclear whether they do so because they are more sensitive to ethanol's rewarding effects or less sensitive to its aversive effects. OBJECTIVE: To further assess the role of GIRK2 in ethanol action, GIRK2 null mutant and wild type mice were tested in conditioning models that measure the motivational effects of ethanol. METHOD: In a conditioned taste aversion (CTA) procedure, knockout and wild type mice were given ethanol (0.0, 2.0, 2.5, or 3.5 g/kg, IP) following 1-h access to saccharin every 48 h over a 10 day period. In a conditioned place preference (CPP) procedure, knockout and wild type mice were given ethanol (2.0 or 3.0 g/kg, IP) paired with one stimulus (grid or hole floor) and saline paired with the other. After four 5-min trials with each stimulus, a 60-min choice test was done. RESULTS: The results demonstrated a genotypic difference in both paradigms. In CTA, there was no difference between genotypes at 0.0 or 3.5 g/kg ethanol, but at the 2.0 and 2.5 g/kg doses, wild types developed a stronger aversion to saccharin than knockouts. In CPP, wild types developed place preference, but knockouts did not. CONCLUSIONS: These studies show that GIRK2 deletion reduced ethanol's impact in tasks that are commonly used to index the drug's rewarding and aversive effects. These findings could reflect either a learning/memory deficit or decreased sensitivity to ethanol's motivational effects in null mutant mice. The latter interpretation is more consistent with previous data showing that knockout mice consume higher doses of ethanol than wild type mice.
Keywords: Animal; Animals; Avoidance Learning; Behavior; Conditioning (Psychology); Ethanol; G Protein-Coupled Inwardly-Rectifying Potassium Channels; Genotype; Inwardly Rectifying; Knockout; Mice; Motivation; Potassium Channels; Reward; Taste

Selective breeding, quantitative trait locus analysis, and gene arrays identify candidate genes for complex drug-related behaviors - Tabakoff, Boris; Bhave, Sanjiv V.; Hoffman, Paula L. (The Journal of Neuroscience: The Official Journal of the Society for Neuroscience, 2003)
Acute functional tolerance to ethanol develops during a single exposure to ethanol; it has been suggested to be a predisposing factor for the development of ethanol dependence. Genetic determinants of acute functional tolerance, as well as of ethanol dependence, have been clearly demonstrated. We describe a novel approach that uses a combination of selective breeding (to segregate genes contributing to the phenotype of interest, i.e., acute functional tolerance to the incoordinating effect of ethanol), quantitative trait locus analysis (to define chromosomal regions associated with acute functional tolerance), and DNA microarray technology (to identify differentially expressed genes in the brains of the selected lines of mice) to identify candidate genes for the complex phenotype of ethanol tolerance. The results indicate the importance of a signal transduction cascade that involves the glutamate receptor delta2 protein, the Ephrin B3 ligand, and the NMDA receptor, as well as a transcriptional regulatory protein that may be induced by activation of the NMDA receptor (zinc finger protein 179) and a protein that can modulate downstream responses to NMDA receptor activation (peroxiredoxin), in mediating acute tolerance to the incoordinating effect of ethanol.
Keywords: Alcohol-Induced Disorders; Animal; Animals; Ataxia; Behavior; Binding Sites; Brain; Breeding; CCAAT-Enhancer-Binding Protein-alpha; Chromosome Mapping; Drug Tolerance; Ethanol; Gene Expression Profiling; Genetic; Genetic Predisposition to Disease; Inbred Strains; Male; Mice; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Postural Balance; Promoter Regions; Quantitative Trait Loci; Transcription Factors

Alcohol and genetics: New models - Crabbe, John C. (American Journal of Medical Genetics, 2002)
Alcoholism is a complex genetic trait; susceptibility is influenced by multiple genes of small effect. To pursue mechanistic studies, genetic animal models have been used. These models are partial, each addressing one or more of the contributing traits rather than the disease as a whole. Animal studies have modeled alcohol's rewarding effects, the development of tolerance, the pathological consequences to brain systems, and the dependence on alcohol inferred from the presence of withdrawal symptoms when the drug is removed. The classical genetic methods of inbred strain analysis and development and studies of selectively bred lines have been employed for more than 40 years. Recently, such studies have shown that a genetic tendency to experience severe withdrawal is associated with a tendency to avoid self-administration of alcohol. Also recently, attempts to identify the specific genes conferring risk or protection from alcohol's effects have been undertaken. These studies have used mapping techniques based on gene sequence polymorphisms, studies of gene expression differences, and the use of candidate gene targeting such as creation of null mutants. Studies reviewed here have mapped quantitative trait loci (QTL) for many genes affecting alcohol sensitivity, tolerance, reward, and withdrawal severity. The furthest progress in gene mapping has been made toward one withdrawal QTL on mouse chromosome 4. Using multiple congenic strains, the gene conferring increased withdrawal severity has been isolated to a region of less than 1 centiMorgan, containing fewer than 20 genes. A strong candidate gene, coding for a multiple PS095/DLG/Z0-1 (PDZ) binding domain zinc finger protein, cannot be excluded. Although many more such genes will be identified in the near future, their contribution to the mapped phenotype will be shown to be dependent on epistatic interactions with other risk genes, as well as genes in the animal's background. Progress in gene identification will also depend crucially on the precise description of the phenotypes being mapped so that their pleiotropic range of influence on the multi-behavioral phenotypic syndrome can be determined. © 2002 Wiley-Liss, Inc.
Keywords: alcoholism; animal models; behavioral genomics; dependence; QTL

DARPP-32 and regulation of the ethanol sensitivity of NMDA receptors in the nucleus accumbens - Maldve, R. E.; Zhang, T. A.; Ferrani-Kile, K.; Schreiber, S. S.; Lippmann, M. J.; Snyder, G. L.; Fienberg, A. A.; Leslie, S. W.; Gonzales, R. A.; Morrisett, R. A. (Nature Neuroscience, 2002)
The medium spiny neurons of the nucleus accumbens receive both an excitatory glutamatergic input from forebrain and a dopaminergic input from the ventral tegmental area. This integration point may constitute a locus whereby the N-methyl-D-aspartate (NMDA)-subtype of glutamate receptors promotes drug reinforcement. Here we investigate how dopaminergic inputs alter the ethanol sensitivity of NMDA receptors in rats and mice and report that previous dopamine receptor-1 (D1) activation, culminating in dopamine and cAMP-regulated phosphoprotein-32 kD (DARPP-32) and NMDA receptor subunit-1 (NR1)-NMDA receptor phosphorylation, strongly decreases ethanol inhibition of NMDA responses. The regulation of ethanol sensitivity of NMDA receptors by D1 receptors was absent in DARPP-32 knockout mice. We propose that DARPP-32 mediated blunting of the response to ethanol subsequent to activation of ventral tegmental area dopaminergic neurons initiates molecular alterations that influence synaptic plasticity in this circuit, thereby promoting the development of ethanol reinforcement.
Keywords: 2; 3; 4; 5-Tetrahydro-7; 8-dihydroxy-1-phenyl-1H-3-benzazepine; Animals; Cyclic AMP; Cyclic AMP-Dependent Protein Kinases; dopamine; Dopamine Agonists; Dopamine and cAMP-Regulated Phosphoprotein 32; Dopamine D1; Ethanol; In Vitro Techniques; Knockout; Mice; N-Methyl-D-Aspartate; Nerve Tissue Proteins; Neuronal Plasticity; Nucleus Accumbens; Phosphoproteins; Phosphorylation; Rats; Receptors; Ventral tegmental area

Ethanol-sensitive sites on the human dopamine transporter - Maiya, Rajani; Buck, Kari J.; Harris, R. Adron; Mayfield, R. Dayne (The Journal of Biological Chemistry, 2002)
Previous studies have shown that ethanol enhanced [(3)H]dopamine uptake in Xenopus oocytes expressing the dopamine transporter (DAT). This increase in DAT activity was mirrored by an increase in the number of transporters expressed at the cell surface. In the present study, ethanol potentiated the function of DAT expressed in HeLa cells but inhibited the function of the related norepinephrine transporter (NET). Chimeras generated between DAT and NET were examined for ethanol sensitivity and demonstrated that a 76-amino acid region spanning transmembrane domains (TMD) 2 and 3 was essential for ethanol potentiation of DAT function. The second intracellular loop between TMD 2 and 3 of DAT, which differs from that of NET by four amino acids, was explored for possible sites of ethanol action. Site-directed mutagenesis was used to replace each of these residues in DAT with the corresponding residue in NET, and the resulting cRNA were expressed in Xenopus oocytes. We found that mutations G130T or I137F abolished ethanol potentiation of DAT function, whereas the mutations F123Y and L138F had no significant effect. These results identify novel sites in the second intracellular loop that are important for ethanol modulation of DAT activity.
Keywords: Animals; dopamine; Dopamine Plasma Membrane Transport Proteins; Ethanol; Female; HeLa Cells; Humans; Membrane Glycoproteins; Membrane Transport Proteins; Mutagenesis; Nerve Tissue Proteins; Norepinephrine Plasma Membrane Transport Proteins; Rats; Site-Directed; Structure-Activity Relationship; Symporters; Xenopus laevis

Hyperactivity and dopamine D1 receptor activation in mice lacking girk2 channels - Blednov, Y.; Stoffel, M.; Cooper, R.; Wallace, D.; Mane, N.; Harris, R. (Psychopharmacology, 2002)
.Rationale: G-protein-coupled inwardly rectifying potassium channels (GIRKs) regulate synaptic transmission and neuronal firing rates. Co-localization of GIRK2 channels and dopamine receptors in the mesolimbic system suggests a role in regulation of motor activity. Objectives: To explore the role of GIRK channels in the regulation of motor behavior. Methods: GIRK2 null mutant mice (knockout) were used. Locomotor activity in a mildly stressful situation was conducted either in a circular open field with video tracking or in standard mouse cages equipped with infrared sensors. Drugs were injected intraperitoneally or subcutaneously. Results: GIRK2 knockout mice demonstrated a transient "hyperactive" behavioral phenotype with initially higher motor activity and slower habituation in a novel situation, increased levels of spontaneous locomotor activity during dark phase in their home cages, and impaired habituation in the open-field test. After habituation, GIRK2 knockout mice showed higher motor activity, which was inhibited by the D1 receptor antagonist SCH 23390 and was more sensitive to the activating effects of the D1 receptor partial agonist SKF 38393. In a novel environment (open-field) only the highest dose of SKF38393 used (20 mg/kg) produced significant activation, perhaps due to a ceiling effect in GIRK2 knockout mice. SCH 23390 inhibited the basal activity levels of mice of both genotypes. Conclusions: Activation of the dopamine D1 receptor in a stressful environment may be stronger in GIRK2 deficient mice, and this modified function of D1 receptors may cause the transient hyperactive behavioral phenotype of these mice.

Patterns of gene expression are altered in the frontal and motor cortices of human alcoholics - Mayfield, R. Dayne; Lewohl, Joanne M.; Dodd, Peter R.; Herlihy, Amy; Liu, Jianwen; Harris, R. Adron (Journal of Neurochemistry, 2002)
Alcoholism is a major health problem in Western countries, yet relatively little is known about the mechanisms by which chronic alcohol abuse causes the pathologic changes associated with the disease. It is likely that chronic alcoholism affects a number of signaling cascades and transcription factors, which in turn result in distinct gene expression patterns. These patterns are difficult to detect by traditional experiments measuring a few mRNAs at a time, but are well suited to microarray analyses. We used cDNA microarrays to analyze expression of approximately 10 000 genes in the frontal and motor cortices of three groups of chronic alcoholic and matched control cases. A functional hierarchy was devised for classification of brain genes and the resulting groups were compared based on differential expression. Comparison of gene expression patterns in these brain regions revealed a selective reprogramming of gene expression in distinct functional groups. The most pronounced differences were found in myelin-related genes and genes involved in protein trafficking. Significant changes in the expression of known alcohol-responsive genes, and genes involved in calcium, cAMP, and thyroid signaling pathways were also identified. These results suggest that multiple pathways may be important for neuropathology and altered neuronal function observed in alcoholism.
Keywords: Adult; Aged; Alcohol Drinking; alcoholism; Chronic Disease; Frontal Lobe; Gene Expression Profiling; Gene Expression Regulation; Humans; Messenger; Middle Aged; Motor Cortex; Myelin Sheath; Oligonucleotide Array Sequence Analysis; Protein Transport; Reference Values; RNA; Signal Transduction

Quantitative Trait Loci Affecting Initial Sensitivity and Acute Functional Tolerance to Ethanol-Induced Ataxia and Brain cAMP Signaling in BXD Recombinant Inbred Mice - Kirstein, Shelli L.; Davidson, Kirsten L.; Ehringer, Marissa A.; Sikela, James M.; Erwin, V. Gene; Tabakoff, Boris (Journal of Pharmacology and Experimental Therapeutics, 2002)
In previous work, we identified genetic correlations between cAMP accumulation in the cerebellum and sensitivity to the incoordinating effects of ethanol. A genetic correlation suggests that common genes underlie the phenotypes investigated. One method for provisionally identifying genes involved in a given phenotypic measure is quantitative trait locus (QTL) analysis. Using a panel of 30 BXD recombinant inbred strains of mice and the progenitors (DBA/2J and C57BL/6J), and the dowel test for ataxia, we measured the blood ethanol concentrations at the time an animal first fell from the dowel and acute functional tolerance (AFT), and investigated cAMP signaling in the cerebellum. Cyclic AMP accumulation was measured in whole-cell preparations of cerebellar minces from individual mice under basal or stimulated conditions. We conducted a genome-wide QTL analysis of the behavioral and biochemical measures with >2000 genetic markers to identify significant associations. Western blot and comparative sequencing analysis were used to compare cAMP response element binding protein (CREB) levels and protein-coding sequence, respectively. QTL analyses correlating strain means with allelic status at genetic markers identified several significant associations (p < 0.01). Analysis of variance revealed an effect of strain on behavioral and biochemical measures. There was a significant genetic correlation between initial sensitivity and basal cAMP accumulation in the cerebellum. We identified 6 provisional QTLs for initial sensitivity on four chromosomes, 6 provisional QTLs for AFT on four chromosomes, and 11 provisional QTLs for cAMP signaling on nine chromosomes. Two loci were found to overlap for measures of initial sensitivity and for cAMP signaling. Given the genetic correlation between initial sensitivity and basal cAMP accumulation, we investigated candidate genes in a QTL on chromosome 1. Comparative sequence analysis was performed, and protein levels were compared between C57 and DBA mice for Creb1. No significant differences were detected in coding sequence or protein levels for CREB. These results suggest that although ethanol sensitivity and cAMP signaling are determined by multiple genes, they may share certain genetic codetermination.

Streamlining microarray technology in a prototype core laboratory - Soriano, Brian; Bean, Pamela; Gaydos, Jeanette; Tabakoff, Boris (American Clinical Laboratory, 2002)
The overall scheme of a microarray experiment is summarized in Figure 3. The real benefit of using microarrays in research is gaining knowledge from the abundant data provided from the series of related microarray experiments. The core laboratory has produced three cDNA arrays, a mouse 15K array, a human 13K array, and a human apoptosis array with 350 plus apoptotic elements. Recently, the 15K array is being used in building a database for gene expression in several areas of the mouse brain and for studying transgenic and knockout mice. The apoptosis array has been used by cancer researchers to further elucidate changes and interactions between genes leading to cell death and cancer. The UCHSC Gene Expression Array Core is supported by the National Institute on Aging and the National Cancer Institute (Bethesda, MD) to serve all academic users and has a special interest in providing a solid technological base for genomic researchers interested in alcohol and cancer research.
Keywords: Animals; Biotechnology; Humans; Laboratories; Mice; Oligonucleotide Array Sequence Analysis

Transgenic Expression of a Mutant Glycine Receptor Decreases Alcohol Sensitivity of Mice - Findlay, G. S.; Wick, M. J.; Mascia, M. P.; Wallace, D.; Miller, G. W.; Harris, R. A.; Blednov, Y. A. (Journal of Pharmacology and Experimental Therapeutics, 2002)
Glycine receptors (GlyRs) are pentameric ligand-gated ion channels that inhibit neurotransmission in the adult brainstem and spinal cord. GlyR function is potentiated by ethanol in vitro, and a mutant GlyR subunit α1(S267Q) is insensitive to the potentiating effects of ethanol. To test the importance of GlyR for the actions of ethanol in vivo, we constructed transgenic mice with this mutation. Under the control of synapsin I regulatory sequences, transgenic expression of S267Q mutant GlyR α1 subunits in the nervous system was demonstrated using [3H]strychnine binding and immunoblotting. These mice showed decreased sensitivity to ethanol in three behavioral tests: ethanol inhibition of strychnine seizures, motor incoordination (rotarod), and loss of righting reflex. There was no change in ethanol sensitivity in tests of acute functional tolerance or body temperature, and there was no change in ethanol metabolism. Transgene effects were pharmacologically specific for ethanol, compared with pentobarbital, flurazepam, and ketamine. These results support the idea that glycine receptors contribute to some behavioral actions of ethanol and that ethanol sensitivity can be changed in vivo by transgenic expression of a single receptor subunit.

On the immortality of the germ line: genetic and biochemical mechanism. A review - Medvedev, Z. A. (Mechanisms of Ageing and Development, 1981)
The nature of the differences between mortal somatic cells and immortal germ cell lines constitutes a major area of theoretical gerontology which has not yet received adequate attention. Weismann's theory, first stated almost exactly a century ago, was recently reconsidered by Kirkwood and Holliday. They applied modern concepts and findings on the factors regulating the accuracy of synthesis of macromolecules to explain germ line immortality. In the present paper, evidence on ageing of reproductive cells and the relationship of cytomorphogenetic events to periodic rejuvenation of germ cell lines is summarized and evaluated. Key events include the elimination or reversal of some DNA changes in germ cells through recombination and meiotic haploidization, cyclic regeneration of transcriptional and translational systems during gametogenesis and early development, and the selection of stable, viable genomes at various stages of the reproductive cycle. These rejuvenatory processes are compared and related to molecular events which differentiated somatic cells are unable to carry out.
Keywords: Aging; Animals; Biological; Biological Evolution; Cell Division; Cell Survival; Cytoplasm; DNA; DNA Repair; Embryo; Female; Genetic; Germ Cells; Haploidy; Humans; Hybridization; Male; Mammalian; Meiosis; Models; Mutation; Oocytes; Oogenesis; Protein Biosynthesis; Reproduction; RNA; Spermatogenesis; Transcription